Absent B cells, agammaglobulinemia, and hypertrophic cardiomyopathy in folliculin-interacting protein 1 deficiency. - Saettini, Francesco; Poli, Cecilia; Vengoechea, Jaime; Bonanomi, Sonia; Orellana, Julio C; Fazio, Grazia; Rodriguez, Fred H; Noguera, Loreani P; Booth, Claire; Jarur-Chamy, Valentina; Shams, Marissa; Iascone, Maria; et al. (Blood, 2021)
Agammaglobulinemia is the most profound primary antibody deficiency that can occur due to an early termination of B-cell development. We here investigated 3 novel patients, including the first known adult, from unrelated families with agammaglobulinemia, recurrent infections, and hypertrophic cardiomyopathy (HCM). Two of them also presented with intermittent or severe chronic neutropenia. We identified homozygous or compound-heterozygous variants in the gene for folliculin interacting protein 1 (FNIP1), leading to loss of the FNIP1 protein. B-cell metabolism, including mitochondrial numbers and activity and phosphatidylinositol 3-kinase/AKT pathway, was impaired. These defects recapitulated the Fnip1-/- animal model. Moreover, we identified either uniparental disomy or copy-number variants (CNVs) in 2 patients, expanding the variant spectrum of this novel inborn error of immunity. The results indicate that FNIP1 deficiency can be caused by complex genetic mechanisms and support the clinical utility of exome sequencing and CNV analysis in patients with broad phenotypes, including agammaglobulinemia and HCM. FNIP1 deficiency is a novel inborn error of immunity characterized by early and severe B-cell development defect, agammaglobulinemia, variable neutropenia, and HCM. Our findings elucidate a functional and relevant role of FNIP1 in B-cell development and metabolism and potentially neutrophil activity.
Keywords: Adult; Agammaglobulinemia; Animals; B-Lymphocytes; Cardiomyopathy, Hypertrophic; Carrier Proteins; Child; Child, Preschool; Chromosomes, Human, Pair 5; Codon, Nonsense; Consanguinity; Crohn Disease; Developmental Disabilities; Disease Models, Animal; Disease Susceptibility; DNA Copy Number Variations; Female; Heart Defects, Congenital; Humans; Immunologic Deficiency Syndromes; Infections; Loss of Function Mutation; Lymphopenia; Male; Mice; Neutropenia; Pedigree; Uniparental Disomy; Whole Exome Sequencing

Accurate, scalable cohort variant calls using DeepVariant and GLnexus. - Yun, Taedong; Li, Helen; Chang, Pi-Chuan; Lin, Michael F; Carroll, Andrew; McLean, Cory Y (Bioinformatics, 2021)
MOTIVATION: Population-scale sequenced cohorts are foundational resources for genetic analyses, but processing raw reads into analysis-ready cohort-level variants remains challenging. RESULTS: We introduce an open-source cohort-calling method that uses the highly-accurate caller DeepVariant and scalable merging tool GLnexus. Using callset quality metrics based on variant recall and precision in benchmark samples and Mendelian consistency in father-mother-child trios, we optimized the method across a range of cohort sizes, sequencing methods, and sequencing depths. The resulting callsets show consistent quality improvements over those generated using existing best practices with reduced cost. We further evaluate our pipeline in the deeply sequenced 1000 Genomes Project (1KGP) samples and show superior callset quality metrics and imputation reference panel performance compared to an independently-generated GATK Best Practices pipeline. AVAILABILITY AND IMPLEMENTATION: We publicly release the 1KGP individual-level variant calls and cohort callset (https://console.cloud.google.com/storage/browser/brain-genomics-public/research/cohort/1KGP) to foster additional development and evaluation of cohort merging methods as well as broad studies of genetic variation. Both DeepVariant (https://github.com/google/deepvariant) and GLnexus (https://github.com/dnanexus-rnd/GLnexus) are open-sourced, and the optimized GLnexus setup discovered in this study is also integrated into GLnexus public releases v1.2.2 and later. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.

Alternative genomic diagnoses for individuals with a clinical diagnosis of Dubowitz syndrome. - Dyment, David A; O'Donnell-Luria, Anne; Agrawal, Pankaj B; Coban Akdemir, Zeynep; Aleck, Kyrieckos A; Antaki, Danny; Al Sharhan, Hind; Au, Ping-Yee B; Aydin, Hatip; Beggs, Alan H; Bilguvar, Kaya; Boerwinkle, Eric; et al. (Am J Med Genet A, 2021)
Dubowitz syndrome (DubS) is considered a recognizable syndrome characterized by a distinctive facial appearance and deficits in growth and development. There have been over 200 individuals reported with Dubowitz or a "Dubowitz-like" condition, although no single gene has been implicated as responsible for its cause. We have performed exome (ES) or genome sequencing (GS) for 31 individuals clinically diagnosed with DubS. After genome-wide sequencing, rare variant filtering and computational and Mendelian genomic analyses, a presumptive molecular diagnosis was made in 13/27 (48%) families. The molecular diagnoses included biallelic variants in SKIV2L, SLC35C1, BRCA1, NSUN2; de novo variants in ARID1B, ARID1A, CREBBP, POGZ, TAF1, HDAC8, and copy-number variation at1p36.11(ARID1A), 8q22.2(VPS13B), Xp22, and Xq13(HDAC8). Variants of unknown significance in known disease genes, and also in genes of uncertain significance, were observed in 7/27 (26%) additional families. Only one gene, HDAC8, could explain the phenotype in more than one family (N = 2). All but two of the genomic diagnoses were for genes discovered, or for conditions recognized, since the introduction of next-generation sequencing. Overall, the DubS-like clinical phenotype is associated with extensive locus heterogeneity and the molecular diagnoses made are for emerging clinical conditions sharing characteristic features that overlap the DubS phenotype.

Association of De Novo Variants With Childhood Onset Moyamoya Disease and Diffuse Occlusive Vasculopathy. - Pinard, Amelie; Fiander, Maximillian D J; Cecchi, Alana C; Rideout, Andrea L; Azouz, Mohamed; Fraser, Stuart M; McNeely, P Daniel; Walling, Simon; Novara, Sarah C; Hurst, Anna C E; Guo, Dongchuan; Parkash, Sandhya; et al. (Neurology, 2021)
OBJECTIVE: To test the hypothesis that de novo genetic variants are responsible for moyamoya disease (MMD) in children with unaffected relatives, we performed exome sequencing of 28 affected children and their unaffected parents. METHODS: Exome sequencing was performed on 28 trios of affected patients with MMD and unaffected parents. RESULTS: We identified 3 novel rare de novo variants, 1 in the RING domain and 2 in a highly conserved region distal to the RING domain (4,114-4,120). These de novo cases of MMD present at a young age with aggressive MMD and uniquely have additional occlusive vascular lesions, including renal artery stenosis. Two previously reported cases had de novo variants in the same limited region and presented young with aggressive MMD, and 1 case had narrowing of the inferior abdominal aorta. CONCLUSIONS: These results indicate a novel syndrome associated with rare variants defined by de novo mutations disrupting highly conserved amino acids in the RING domain and a discrete region distal to the RING domain delimited by amino acids 4,114 to 4,120 leading to onset of severe MMD before 3 years of age and occlusion of other arteries, including the abdominal aorta, renal, iliac, and femoral arteries.
Keywords: Adenosine Triphosphatases; Adult; Age of Onset; Aortic Diseases; Arterial Occlusive Diseases; Child, Preschool; Female; Femoral Artery; Humans; Iliac Artery; Male; Moyamoya Disease; Mutation; Renal Artery Obstruction; Ubiquitin-Protein Ligases

Association of Genetic Variation With Cirrhosis: A Multi-Trait Genome-Wide Association and Gene-Environment Interaction Study. - Emdin, Connor A; Haas, Mary; Ajmera, Veeral; Simon, Tracey G; Homburger, Julian; Neben, Cynthia; Jiang, Lan; Wei, Wei-Qi; Feng, Qiping; Zhou, Alicia; Denny, Joshua; Corey, Kathleen; et al. (Gastroenterology, 2021)
BACKGROUND & AIMS: In contrast to most other common diseases, few genetic variants have been identified that impact risk of cirrhosis. We aimed to identify new genetic variants that predispose to cirrhosis, to test whether such variants, aggregated into a polygenic score, enable genomic risk stratification, and to test whether alcohol intake or body mass index interacts with polygenic predisposition. METHODS: We conducted a multi-trait genome-wide association study combining cirrhosis and alanine aminotransferase levels performed in 5 discovery studies (UK Biobank, Vanderbilt BioVU, Atherosclerosis Risk in Communities study, and 2 case-control studies including 4829 individuals with cirrhosis and 72,705 controls and 362,539 individuals with alanine aminotransferase levels). Identified variants were replicated in 3 studies (Partners HealthCare Biobank, FinnGen, and Biobank Japan including 3554 individuals with cirrhosis and 343,826 controls). A polygenic score was tested in Partners HealthCare Biobank. RESULTS: Five previously reported and 7 newly identified genetic variants were associated with cirrhosis in both the discovery studies multi-trait genome-wide association study (P < 5 × 10) and the replication studies (P < .05), including a missense variant in the APOE gene and a noncoding variant near EFN1A. These 12 variants were used to generate a polygenic score. Among Partners HealthCare Biobank individuals, high polygenic score-defined as the top quintile of the distribution-was associated with significantly increased risk of cirrhosis (odds ratio, 2.26; P < .001) and related comorbidities compared with the lowest quintile. Risk was even more pronounced among those with extreme polygenic risk (top 1% of the distribution, odds ratio, 3.16; P < .001). The impact of extreme polygenic risk was substantially more pronounced in those with elevated alcohol consumption or body mass index. Modeled as risk by age 75 years, probability of cirrhosis with extreme polygenic risk was 13.7%, 20.1%, and 48.2% among individuals with no or modest, moderate, and increased alcohol consumption, respectively (P < .001). Similarly, probability among those with extreme polygenic risk was 6.5%, 10.3%, and 19.5% among individuals with normal weight, overweight, and obesity, respectively (P < .001). CONCLUSIONS: Twelve independent genetic variants, 7 of which are newly identified in this study, conferred risk for cirrhosis. Aggregated into a polygenic score, these variants identified a subset of the population at substantially increased risk who are most susceptible to the hepatotoxic effects of excess alcohol consumption or obesity.

Association of structural variation with cardiometabolic traits in Finns. - Chen, Lei; Abel, Haley J; Das, Indraniel; Larson, David E; Ganel, Liron; Kanchi, Krishna L; Regier, Allison A; Young, Erica P; Kang, Chul Joo; Scott, Alexandra J; Chiang, Colby; Wang, Xinxin; et al. (Am J Hum Genet, 2021)
The contribution of genome structural variation (SV) to quantitative traits associated with cardiometabolic diseases remains largely unknown. Here, we present the results of a study examining genetic association between SVs and cardiometabolic traits in the Finnish population. We used sensitive methods to identify and genotype 129,166 high-confidence SVs from deep whole-genome sequencing (WGS) data of 4,848 individuals. We tested the 64,572 common and low-frequency SVs for association with 116 quantitative traits and tested candidate associations using exome sequencing and array genotype data from an additional 15,205 individuals. We discovered 31 genome-wide significant associations at 15 loci, including 2 loci at which SVs have strong phenotypic effects: (1) a deletion of the ALB promoter that is greatly enriched in the Finnish population and causes decreased serum albumin level in carriers (p = 1.47 × 10) and is also associated with increased levels of total cholesterol (p = 1.22 × 10) and 14 additional cholesterol-related traits, and (2) a multi-allelic copy number variant (CNV) at PDPR that is strongly associated with pyruvate (p = 4.81 × 10) and alanine (p = 6.14 × 10) levels and resides within a structurally complex genomic region that has accumulated many rearrangements over evolutionary time. We also confirmed six previously reported associations, including five led by stronger signals in single nucleotide variants (SNVs) and one linking recurrent HP gene deletion and cholesterol levels (p = 6.24 × 10), which was also found to be strongly associated with increased glycoprotein level (p = 3.53 × 10). Our study confirms that integrating SVs in trait-mapping studies will expand our knowledge of genetic factors underlying disease risk.
Keywords: Alleles; Cardiovascular Diseases; Cholesterol; DNA Copy Number Variations; Female; Finland; Genome, Human; Genomic Structural Variation; Genotype; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Promoter Regions, Genetic; Pyruvate Dehydrogenase (Lipoamide)-Phosphatase; Pyruvic Acid; Serum Albumin, Human

Auto-antibodies to type I IFNs can underlie adverse reactions to yellow fever live attenuated vaccine. - Bastard, Paul; Michailidis, Eleftherios; Hoffmann, Hans-Heinrich; Chbihi, Marwa; Le Voyer, Tom; Rosain, Jérémie; Philippot, Quentin; Seeleuthner, Yoann; Gervais, Adrian; Materna, Marie; de Oliveira, Patricia Mouta Nunes; Maia, Maria de Lourdes S; et al. (J Exp Med, 2021)
Yellow fever virus (YFV) live attenuated vaccine can, in rare cases, cause life-threatening disease, typically in patients with no previous history of severe viral illness. Autosomal recessive (AR) complete IFNAR1 deficiency was reported in one 12-yr-old patient. Here, we studied seven other previously healthy patients aged 13 to 80 yr with unexplained life-threatening YFV vaccine-associated disease. One 13-yr-old patient had AR complete IFNAR2 deficiency. Three other patients vaccinated at the ages of 47, 57, and 64 yr had high titers of circulating auto-Abs against at least 14 of the 17 individual type I IFNs. These antibodies were recently shown to underlie at least 10% of cases of life-threatening COVID-19 pneumonia. The auto-Abs were neutralizing in vitro, blocking the protective effect of IFN-α2 against YFV vaccine strains. AR IFNAR1 or IFNAR2 deficiency and neutralizing auto-Abs against type I IFNs thus accounted for more than half the cases of life-threatening YFV vaccine-associated disease studied here. Previously healthy subjects could be tested for both predispositions before anti-YFV vaccination.
Keywords: Adolescent; Adult; Aged; Antibodies, Neutralizing; Autoantibodies; Autoimmune Diseases; COVID-19; Female; Genetic Diseases, Inborn; HEK293 Cells; Humans; Interferon-alpha; Male; Middle Aged; Receptor, Interferon alpha-beta; SARS-CoV-2; Vaccines, Attenuated; Yellow Fever Vaccine; Yellow fever virus

Autosomal recessive variants in alter the γ-tubulin ring complex leading to neurodevelopmental disease. - Güngör, Serdal; Oktay, Yavuz; Hiz, Semra; Aranguren-Ibáñez, Álvaro; Kalafatcilar, Ipek; Yaramis, Ahmet; Karaca, Ezgi; Yis, Uluc; Sonmezler, Ece; Ekinci, Burcu; Aslan, Mahmut; Yilmaz, Elmasnur; et al. (iScience, 2021)
Microtubules help building the cytoskeleton of neurons and other cells. Several components of the gamma-tubulin (γ-tubulin) complex have been previously reported in human neurodevelopmental diseases. We describe two siblings from a consanguineous Turkish family with dysmorphic features, developmental delay, brain malformation, and epilepsy carrying a homozygous mutation (p.Glu311Lys) in encoding the γ-tubulin complex 2 (GCP2) protein. This variant is predicted to disrupt the electrostatic interaction of GCP2 with GCP3. In primary fibroblasts carrying the variant, we observed a faint delocalization of γ-tubulin during the cell cycle but normal GCP2 protein levels. Through mass spectrometry, we observed dysregulation of multiple proteins involved in the assembly and organization of the cytoskeleton and the extracellular matrix, controlling cellular adhesion and of proteins crucial for neuronal homeostasis including axon guidance. In summary, our functional and proteomic studies link TUBGCP2 and the γ-tubulin complex to the development of the central nervous system in humans.

Biallelic variants in HPDL, encoding 4-hydroxyphenylpyruvate dioxygenase-like protein, lead to an infantile neurodegenerative condition. - Ghosh, Shereen G; Lee, Sangmoon; Fabunan, Rudy; Chai, Guoliang; Zaki, MAH S; Abdel-Salam, Ghada; Sultan, Tipu; Ben-Omran, Tawfeg; Alvi, Javeria Raza; McEvoy-Venneri, Jennifer; Stanley, Valentina; Patel, Aakash; et al. (Genet Med, 2021)
PURPOSE: Dioxygenases are oxidoreductase enzymes with roles in metabolic pathways necessary for aerobic life. 4-hydroxyphenylpyruvate dioxygenase-like protein (HPDL), encoded by HPDL, is an orphan paralogue of 4-hydroxyphenylpyruvate dioxygenase (HPD), an iron-dependent dioxygenase involved in tyrosine catabolism. The function and association of HPDL with human diseases remain unknown. METHODS: We applied exome sequencing in a cohort of over 10,000 individuals with neurodevelopmental diseases. Effects of HPDL loss were investigated in vitro and in vivo, and through mass spectrometry analysis. Evolutionary analysis was performed to investigate the potential functional separation of HPDL from HPD. RESULTS: We identified biallelic variants in HPDL in eight families displaying recessive inheritance. Knockout mice closely phenocopied humans and showed evidence of apoptosis in multiple cellular lineages within the cerebral cortex. HPDL is a single-exonic gene that likely arose from a retrotransposition event at the base of the tetrapod lineage, and unlike HPD, HPDL is mitochondria-localized. Metabolic profiling of HPDL mutant cells and mice showed no evidence of altered tyrosine metabolites, but rather notable accumulations in other metabolic pathways. CONCLUSION: The mitochondrial localization, along with its disrupted metabolic profile, suggests HPDL loss in humans links to a unique neurometabolic mitochondrial infantile neurodegenerative condition.
Keywords: 4-Hydroxyphenylpyruvate Dioxygenase; Animals; Dioxygenases; Exons; Mice; Mice, Knockout; Phenotype

Chromosome-scale, haplotype-resolved assembly of human genomes. - Garg, Shilpa; Fungtammasan, Arkarachai; Carroll, Andrew; Chou, Mike; Schmitt, Anthony; Zhou, Xiang; Mac, Stephen; Peluso, Paul; Hatas, Emily; Ghurye, Jay; Maguire, Jared; Mahmoud, Medhat; et al. (Nat Biotechnol, 2021)
Haplotype-resolved or phased genome assembly provides a complete picture of genomes and their complex genetic variations. However, current algorithms for phased assembly either do not generate chromosome-scale phasing or require pedigree information, which limits their application. We present a method named diploid assembly (DipAsm) that uses long, accurate reads and long-range conformation data for single individuals to generate a chromosome-scale phased assembly within 1 day. Applied to four public human genomes, PGP1, HG002, NA12878 and HG00733, DipAsm produced haplotype-resolved assemblies with minimum contig length needed to cover 50% of the known genome (NG50) up to 25 Mb and phased ~99.5% of heterozygous sites at 98-99% accuracy, outperforming other approaches in terms of both contiguity and phasing completeness. We demonstrate the importance of chromosome-scale phased assemblies for the discovery of structural variants (SVs), including thousands of new transposon insertions, and of highly polymorphic and medically important regions such as the human leukocyte antigen (HLA) and killer cell immunoglobulin-like receptor (KIR) regions. DipAsm will facilitate high-quality precision medicine and studies of individual haplotype variation and population diversity.
Keywords: Algorithms; Chromosomes, Human; Genome, Human; Haplotypes; Heterozygote; Humans; Polymorphism, Single Nucleotide

Clinical and molecular evaluation of 13 Brazilian patients with Gomez-López-Hernández syndrome. - Perrone, Eduardo; Perez, Ana Beatriz Alvarez; D'Almeida, Vânia; de Mello, Claudia Berlim; Jacobina, Marcela Amaral Avelino; Loureiro, Rafael Maffei; Burlin, Stênio; Migliavacca, Michele; do Amaral Virmond, Luiza; Graziadio, Carla; Pedroso, José Luiz; Mendes, Elaine Lustosa; et al. (Am J Med Genet A, 2021)
We aim to characterize patients with Gomez-López-Hernández syndrome (GLHS) clinically and to investigate them molecularly. A clinical protocol, including a morphological and neuropsychological assessment, was applied to 13 patients with GLHS. Single-nucleotide polymorphism (SNP) array and whole-exome sequencing were undertaken; magnetic resonance imaging was performed in 12 patients, including high-resolution, heavily T2-weighted sequences (HRT2) in 6 patients to analyze the trigeminal nerves. All patients presented alopecia; two did not present rhombencephalosynapsis (RES); trigeminal anesthesia was present in 5 of the 11 patients (45.4%); brachycephaly/brachyturricephaly and mid-face retrusion were found in 84.6 and 92.3% of the patients, respectively. One patient had intellectual disability. HRT2 sequences showed trigeminal nerve hypoplasia in four of the six patients; all four had clinical signs of trigeminal anesthesia. No common candidate gene was found to explain GLHS phenotype. RES does not seem to be an obligatory finding in respect of GLHS diagnosis. We propose that a diagnosis of GLHS should be considered in patients with at least two of the following criteria: focal non-scarring alopecia, rhombencephalosynapsis, craniofacial anomalies (brachyturrycephaly, brachycephaly or mid-face retrusion), trigeminal anesthesia or anatomic abnormalities of the trigeminal nerve. Studies focusing on germline whole genome sequencing or DNA and/or RNA sequencing of the alopecia tissue may be the next step for the better understanding of GLHS etiology.

Clinical presentation and evolution of Xia-Gibbs syndrome due to p.Gly375ArgfsTer3 variant in a patient from DR Congo (Central Africa). - Mubungu, Gerrye; Makay, Prince; Boujemla, Bouchra; Yanda, Stephane; Posey, Jennifer E; Lupski, James R; Bours, Vincent; Lukusa, Prosper; Devriendt, Koenraad; Lumaka, Aimé (Am J Med Genet A, 2021)
Xia-Gibbs syndrome (XGS) is a very rare genetic condition. The clinical spectrum is very broad and variable. The phenotype and evolution in a Congolese boy with XGS have been reported. At 6 years he had speech delay, drooling, marked hyperactivity, attention deficit, aggressive behavior, and intellectual disability. Dysmorphological evaluation revealed strabismus, mild unilateral ptosis, uplifted ear lobes, flat philtrum, thin upper lip vermillion, high arched palate, and flat feet. Patient-only whole exome sequencing identified a known pathogenic frameshift variant in the AHDC1 gene [NM_001029882.3(AHDC1):c.1122dupC;(p.Gly375ArgfsTer3)]. The clinical follow-up revealed the deterioration of his fine motor skills and significant cerebellar phenotype including tremor, pes cavus, and gait instability at the age of 12 years. This patient was compared with three previously reported patients with the same variant but did not identify a consistent pattern in the evolution of symptoms with age.

Constrained chromatin accessibility in PU.1-mutated agammaglobulinemia patients. - Le Coz, Carole; Nguyen, David N; Su, Chun; Nolan, Brian E; Albrecht, Amanda V; Xhani, Suela; Sun, Di; Demaree, Benjamin; Pillarisetti, Piyush; Khanna, Caroline; Wright, Francis; Chen, Peixin Amy; et al. (J Exp Med, 2021)
The pioneer transcription factor (TF) PU.1 controls hematopoietic cell fate by decompacting stem cell heterochromatin and allowing nonpioneer TFs to enter otherwise inaccessible genomic sites. PU.1 deficiency fatally arrests lymphopoiesis and myelopoiesis in mice, but human congenital PU.1 disorders have not previously been described. We studied six unrelated agammaglobulinemic patients, each harboring a heterozygous mutation (four de novo, two unphased) of SPI1, the gene encoding PU.1. Affected patients lacked circulating B cells and possessed few conventional dendritic cells. Introducing disease-similar SPI1 mutations into human hematopoietic stem and progenitor cells impaired early in vitro B cell and myeloid cell differentiation. Patient SPI1 mutations encoded destabilized PU.1 proteins unable to nuclear localize or bind target DNA. In PU.1-haploinsufficient pro-B cell lines, euchromatin was less accessible to nonpioneer TFs critical for B cell development, and gene expression patterns associated with the pro- to pre-B cell transition were undermined. Our findings molecularly describe a novel form of agammaglobulinemia and underscore PU.1's critical, dose-dependent role as a hematopoietic euchromatin gatekeeper.

CSNK2B: A broad spectrum of neurodevelopmental disability and epilepsy severity. - Ernst, Michelle E; Baugh, Evan H; Thomas, Amanda; Bier, Louise; Lippa, Natalie; Stong, Nicholas; Mulhern, Maureen S; Kushary, Sulagna; Akman, Cigdem I; Heinzen, Erin L; Yeh, Raymond; Bi, Weimin; et al. (Epilepsia, 2021)
CSNK2B has recently been implicated as a disease gene for neurodevelopmental disability (NDD) and epilepsy. Information about developmental outcomes has been limited by the young age and short follow-up for many of the previously reported cases, and further delineation of the spectrum of associated phenotypes is needed. We present 25 new patients with variants in CSNK2B and refine the associated NDD and epilepsy phenotypes. CSNK2B variants were identified by research or clinical exome sequencing, and investigators from different centers were connected via GeneMatcher. Most individuals had developmental delay and generalized epilepsy with onset in the first 2 years. However, we found a broad spectrum of phenotypic severity, ranging from early normal development with pharmacoresponsive seizures to profound intellectual disability with intractable epilepsy and recurrent refractory status epilepticus. These findings suggest that CSNK2B should be considered in the diagnostic evaluation of patients with a broad range of NDD with treatable or intractable seizures.

De novo TRIM8 variants impair its protein localization to nuclear bodies and cause developmental delay, epilepsy, and focal segmental glomerulosclerosis. - Weng, Patricia L; Majmundar, Amar J; Khan, Kamal; Lim, Tze Y; Shril, Shirlee; Jin, Gina; Musgrove, John; Wang, Minxian; Ahram, Dina F; Aggarwal, Vimla S; Bier, Louise E; Heinzen, Erin L; et al. (Am J Hum Genet, 2021)
Focal segmental glomerulosclerosis (FSGS) is the main pathology underlying steroid-resistant nephrotic syndrome (SRNS) and a leading cause of chronic kidney disease. Monogenic forms of pediatric SRNS are predominantly caused by recessive mutations, while the contribution of de novo variants (DNVs) to this trait is poorly understood. Using exome sequencing (ES) in a proband with FSGS/SRNS, developmental delay, and epilepsy, we discovered a nonsense DNV in TRIM8, which encodes the E3 ubiquitin ligase tripartite motif containing 8. To establish whether TRIM8 variants represent a cause of FSGS, we aggregated exome/genome-sequencing data for 2,501 pediatric FSGS/SRNS-affected individuals and 48,556 control subjects, detecting eight heterozygous TRIM8 truncating variants in affected subjects but none in control subjects (p = 3.28 × 10). In all six cases with available parental DNA, we demonstrated de novo inheritance (p = 2.21 × 10). Reverse phenotyping revealed neurodevelopmental disease in all eight families. We next analyzed ES from 9,067 individuals with epilepsy, yielding three additional families with truncating TRIM8 variants. Clinical review revealed FSGS in all. All TRIM8 variants cause protein truncation clustering within the last exon between residues 390 and 487 of the 551 amino acid protein, indicating a correlation between this syndrome and loss of the TRIM8 C-terminal region. Wild-type TRIM8 overexpressed in immortalized human podocytes and neuronal cells localized to nuclear bodies, while constructs harboring patient-specific variants mislocalized diffusely to the nucleoplasm. Co-localization studies demonstrated that Gemini and Cajal bodies frequently abut a TRIM8 nuclear body. Truncating TRIM8 DNVs cause a neuro-renal syndrome via aberrant TRIM8 localization, implicating nuclear bodies in FSGS and developmental brain disease.
Keywords: Adult; Animals; Carrier Proteins; Cell Line; Child; Child, Preschool; Codon, Nonsense; Developmental Disabilities; Epilepsy; Female; Glomerulosclerosis, Focal Segmental; Humans; Intranuclear Space; Kidney; Male; Mice; Mutation; Nephrotic Syndrome; Nerve Tissue Proteins; Phenotype; Podocytes; Whole Exome Sequencing

De novo variants in SNAP25 cause an early-onset developmental and epileptic encephalopathy. - Klöckner, Chiara; Sticht, Heinrich; Zacher, Pia; Popp, Bernt; Babcock, Holly E; Bakker, Dewi P; Barwick, Katy; Bonfert, Michaela V; Bönnemann, Carsten G; Brilstra, Eva H; Chung, Wendy K; Clarke, Angus J; et al. (Genet Med, 2021)
PURPOSE: This study aims to provide a comprehensive description of the phenotypic and genotypic spectrum of SNAP25 developmental and epileptic encephalopathy (SNAP25-DEE) by reviewing newly identified and previously reported individuals. METHODS: Individuals harboring heterozygous missense or loss-of-function variants in SNAP25 were assembled through collaboration with international colleagues, matchmaking platforms, and literature review. For each individual, detailed phenotyping, classification, and structural modeling of the identified variant were performed. RESULTS: The cohort comprises 23 individuals with pathogenic or likely pathogenic de novo variants in SNAP25. Intellectual disability and early-onset epilepsy were identified as the core symptoms of SNAP25-DEE, with recurrent findings of movement disorders, cerebral visual impairment, and brain atrophy. Structural modeling for all variants predicted possible functional defects concerning SNAP25 or impaired interaction with other components of the SNARE complex. CONCLUSION: We provide a comprehensive description of SNAP25-DEE with intellectual disability and early-onset epilepsy mostly occurring before the age of two years. These core symptoms and additional recurrent phenotypes show an overlap to genes encoding other components or associated proteins of the SNARE complex such as STX1B, STXBP1, or VAMP2. Thus, these findings advance the concept of a group of neurodevelopmental disorders that may be termed "SNAREopathies."
Keywords: Brain Diseases; Child, Preschool; Epilepsy; Humans; Intellectual Disability; Neurodevelopmental Disorders; Phenotype; Synaptosomal-Associated Protein 25

De novo variants in TCF7L2 are associated with a syndromic neurodevelopmental disorder. - Dias, Caroline; Pfundt, Rolph; Kleefstra, Tjitske; Shuurs-Hoeijmakers, Janneke; Boon, Elles M J; van Hagen, Johanna M; Zwijnenburg, Petra; Weiss, Marjan M; Keren, Boris; Mignot, Cyril; Isapof, Arnaud; Weiss, Karin; et al. (Am J Med Genet A, 2021)
TCF7L2 encodes transcription factor 7-like 2 (OMIM 602228), a key mediator of the evolutionary conserved canonical Wnt signaling pathway. Although several large-scale sequencing studies have implicated TCF7L2 in intellectual disability and autism, both the genetic mechanism and clinical phenotype have remained incompletely characterized. We present here a comprehensive genetic and phenotypic description of 11 individuals who have been identified to carry de novo variants in TCF7L2, both truncating and missense. Missense variation is clustered in or near a high mobility group box domain, involving this region in these variants' pathogenicity. All affected individuals present with developmental delays in childhood, but most ultimately achieved normal intelligence or had only mild intellectual disability. Myopia was present in approximately half of the individuals, and some individuals also possessed dysmorphic craniofacial features, orthopedic abnormalities, or neuropsychiatric comorbidities including autism and attention-deficit/hyperactivity disorder (ADHD). We thus present an initial clinical and genotypic spectrum associated with variation in TCF7L2, which will be important in informing both medical management and future research.

Deforming Polyarthritis in a North Indian Family-Clinical Expansion of STING-Associated Vasculopathy with Onset in Infancy (SAVI). - Anjani, Gummadi; Jindal, Ankur Kumar; Prithvi, Ashwini; Kaur, Anit; Rawat, Amit; Sharma, Madhubala; Yuan, Bo; Chinn, Ivan K; Singh, Surjit (J Clin Immunol, 2021)

Deletion of CTCF sites in the SHH locus alters enhancer-promoter interactions and leads to acheiropodia. - Ushiki, Aki; Zhang, Yichi; Xiong, Chenling; Zhao, Jingjing; Georgakopoulos-Soares, Ilias; Kane, Lauren; Jamieson, Kirsty; Bamshad, Michael J; Nickerson, Deborah A; Shen, Yin; Lettice, Laura A; Silveira-Lucas, Elizabeth Lemos; et al. (Nat Commun, 2021)
Acheiropodia, congenital limb truncation, is associated with homozygous deletions in the LMBR1 gene around ZRS, an enhancer regulating SHH during limb development. How these deletions lead to this phenotype is unknown. Using whole-genome sequencing, we fine-mapped the acheiropodia-associated region to 12 kb and show that it does not function as an enhancer. CTCF and RAD21 ChIP-seq together with 4C-seq and DNA FISH identify three CTCF sites within the acheiropodia-deleted region that mediate the interaction between the ZRS and the SHH promoter. This interaction is substituted with other CTCF sites centromeric to the ZRS in the disease state. Mouse knockouts of the orthologous 12 kb sequence have no apparent abnormalities, showcasing the challenges in modelling CTCF alterations in animal models due to inherent motif differences between species. Our results show that alterations in CTCF motifs can lead to a Mendelian condition due to altered enhancer-promoter interactions.
Keywords: Animals; Binding Sites; CCCTC-Binding Factor; Chromatin Immunoprecipitation Sequencing; Disease Models, Animal; Embryo, Mammalian; Enhancer Elements, Genetic; Exons; Extremities; Female; Foot Deformities, Congenital; Gene Expression Regulation, Developmental; Genetic Loci; Genetic Testing; Hand Deformities, Congenital; Hedgehog Proteins; Humans; Introns; Male; Membrane Proteins; Mice; Mice, Knockout; Promoter Regions, Genetic; Sequence Deletion; Species Specificity; Whole Genome Sequencing

Detection of homozygous and hemizygous complete or partial exon deletions by whole-exome sequencing. - Bigio, Benedetta; Seeleuthner, Yoann; Kerner, Gaspard; Migaud, Mélanie; Rosain, Jérémie; Boisson, Bertrand; Nasca, Carla; Puel, Anne; Bustamante, Jacinta; Casanova, Jean-Laurent; Abel, Laurent; Cobat, Aurelie (NAR Genom Bioinform, 2021)
The detection of copy number variations (CNVs) in whole-exome sequencing (WES) data is important, as CNVs may underlie a number of human genetic disorders. The recently developed HMZDelFinder algorithm can detect rare homozygous and hemizygous (HMZ) deletions in WES data more effectively than other widely used tools. Here, we present HMZDelFinder_opt, an approach that outperforms HMZDelFinder for the detection of HMZ deletions, including partial exon deletions in particular, in WES data from laboratory patient collections that were generated over time in different experimental conditions. We show that using an optimized reference control set of WES data, based on a PCA-derived Euclidean distance for coverage, strongly improves the detection of HMZ complete exon deletions both in real patients carrying validated disease-causing deletions and in simulated data. Furthermore, we develop a sliding window approach enabling HMZDelFinder_opt to identify HMZ partial deletions of exons that are undiscovered by HMZDelFinder. HMZDelFinder_opt is a timely and powerful approach for detecting HMZ deletions, particularly partial exon deletions, in WES data from inherently heterogeneous laboratory patient collections.

Diagnostic yield and clinical impact of exome sequencing in early-onset scoliosis (EOS). - Zhao, Sen; Zhang, Yuanqiang; Chen, Weisheng; Li, Weiyu; Wang, Shengru; Wang, Lianlei; Zhao, Yanxue; Lin, Mao; Ye, Yongyu; Lin, Jiachen; Zheng, Yu; Liu, Jiaqi; et al. (J Med Genet, 2021)
BACKGROUND: Early-onset scoliosis (EOS), defined by an onset age of scoliosis less than 10 years, conveys significant health risk to affected children. Identification of the molecular aetiology underlying patients with EOS could provide valuable information for both clinical management and prenatal screening. METHODS: In this study, we consecutively recruited a cohort of 447 Chinese patients with operative EOS. We performed exome sequencing (ES) screening on these individuals and their available family members (totaling 670 subjects). Another cohort of 13 patients with idiopathic early-onset scoliosis (IEOS) from the USA who underwent ES was also recruited. RESULTS: After ES data processing and variant interpretation, we detected molecular diagnostic variants in 92 out of 447 (20.6%) Chinese patients with EOS, including 8 patients with molecular confirmation of their clinical diagnosis and 84 patients with molecular diagnoses of previously unrecognised diseases underlying scoliosis. One out of 13 patients with IEOS from the US cohort was molecularly diagnosed. The age at presentation, the number of organ systems involved and the Cobb angle were the three top features predictive of a molecular diagnosis. CONCLUSION: ES enabled the molecular diagnosis/classification of patients with EOS. Specific clinical features/feature pairs are able to indicate the likelihood of gaining a molecular diagnosis through ES.

Diverse genetic causes of polymicrogyria with epilepsy. (Epilepsia, 2021)
OBJECTIVE: We sought to identify novel genes and to establish the contribution of known genes in a large cohort of patients with nonsyndromic sporadic polymicrogyria and epilepsy. METHODS: We enrolled participants with polymicrogyria and their parents through the Epilepsy Phenome/Genome Project. We performed phenotyping and whole exome sequencing (WES), trio analysis, and gene-level collapsing analysis to identify de novo or inherited variants, including germline or mosaic (postzygotic) single nucleotide variants, small insertion-deletion (indel) variants, and copy number variants present in leukocyte-derived DNA. RESULTS: Across the cohort of 86 individuals with polymicrogyria and epilepsy, we identified seven with pathogenic or likely pathogenic variants in PIK3R2, including four germline and three mosaic variants. PIK3R2 was the only gene harboring more than expected de novo variants across the entire cohort, and likewise the only gene that passed the genome-wide threshold of significance in the gene-level rare variant collapsing analysis. Consistent with previous reports, the PIK3R2 phenotype consisted of bilateral polymicrogyria concentrated in the perisylvian region with macrocephaly. Beyond PIK3R2, we also identified one case each with likely causal de novo variants in CCND2 and DYNC1H1 and biallelic variants in WDR62, all genes previously associated with polymicrogyria. Candidate genetic explanations in this cohort included single nucleotide de novo variants in other epilepsy-associated and neurodevelopmental disease-associated genes (SCN2A in two individuals, GRIA3, CACNA1C) and a 597-kb deletion at 15q25, a neurodevelopmental disease susceptibility locus. SIGNIFICANCE: This study confirms germline and postzygotically acquired de novo variants in PIK3R2 as an important cause of bilateral perisylvian polymicrogyria, notably with macrocephaly. In total, trio-based WES identified a genetic diagnosis in 12% and a candidate diagnosis in 6% of our polymicrogyria cohort. Our results suggest possible roles for SCN2A, GRIA3, CACNA1C, and 15q25 deletion in polymicrogyria, each already associated with epilepsy or other neurodevelopmental conditions without brain malformations. The role of these genes in polymicrogyria will be further understood as more patients with polymicrogyria undergo genetic evaluation.

DLG4-related synaptopathy: a new rare brain disorder. - Rodríguez-Palmero, Agustí; Boerrigter, Melissa Maria; Gómez-Andrés, David; Aldinger, Kimberly A; Marcos-Alcalde, Íñigo; Popp, Bernt; Everman, David B; Lovgren, Alysia Kern; Arpin, Stephanie; Bahrambeigi, Vahid; Beunders, Gea; Bisgaard, Anne-Marie; et al. (Genet Med, 2021)
PURPOSE: Postsynaptic density protein-95 (PSD-95), encoded by DLG4, regulates excitatory synaptic function in the brain. Here we present the clinical and genetic features of 53 patients (42 previously unpublished) with DLG4 variants. METHODS: The clinical and genetic information were collected through GeneMatcher collaboration. All the individuals were investigated by local clinicians and the gene variants were identified by clinical exome/genome sequencing. RESULTS: The clinical picture was predominated by early onset global developmental delay, intellectual disability, autism spectrum disorder, and attention deficit-hyperactivity disorder, all of which point to a brain disorder. Marfanoid habitus, which was previously suggested to be a characteristic feature of DLG4-related phenotypes, was found in only nine individuals and despite some overlapping features, a distinct facial dysmorphism could not be established. Of the 45 different DLG4 variants, 39 were predicted to lead to loss of protein function and the majority occurred de novo (four with unknown origin). The six missense variants identified were suggested to lead to structural or functional changes by protein modeling studies. CONCLUSION: The present study shows that clinical manifestations associated with DLG4 overlap with those found in other neurodevelopmental disorders of synaptic dysfunction; thus, we designate this group of disorders as DLG4-related synaptopathy.
Keywords: Autism Spectrum Disorder; Brain; Brain Diseases; Disks Large Homolog 4 Protein; Humans; Intellectual Disability; Neurodevelopmental Disorders; Phenotype

A DNA repair disorder caused by de novo monoallelic DDB1 variants is associated with a neurodevelopmental syndrome. - White, Susan M; Bhoj, Elizabeth; Nellaker, Christoffer; Lachmeijer, Augusta M A; Marshall, Aren E; Boycott, Kym M; Li, Dong; Smith, Wendy; Hartley, Taila; McBride, Arran; Ernst, Michelle E; May, Alison S; et al. (Am J Hum Genet, 2021)
The DNA damage-binding protein 1 (DDB1) is part of the CUL4-DDB1 ubiquitin E3 ligase complex (CRL4), which is essential for DNA repair, chromatin remodeling, DNA replication, and signal transduction. Loss-of-function variants in genes encoding the complex components CUL4 and PHIP have been reported to cause syndromic intellectual disability with hypotonia and obesity, but no phenotype has been reported in association with DDB1 variants. Here, we report eight unrelated individuals, identified through Matchmaker Exchange, with de novo monoallelic variants in DDB1, including one recurrent variant in four individuals. The affected individuals have a consistent phenotype of hypotonia, mild to moderate intellectual disability, and similar facies, including horizontal or slightly bowed eyebrows, deep-set eyes, full cheeks, a short nose, and large, fleshy and forward-facing earlobes, demonstrated in the composite face generated from the cohort. Digital anomalies, including brachydactyly and syndactyly, were common. Three older individuals have obesity. We show that cells derived from affected individuals have altered DDB1 function resulting in abnormal DNA damage signatures and histone methylation following UV-induced DNA damage. Overall, our study adds to the growing family of neurodevelopmental phenotypes mediated by disruption of the CRL4 ubiquitin ligase pathway and begins to delineate the phenotypic and molecular effects of DDB1 misregulation.
Keywords: Adolescent; Alleles; Child; Child, Preschool; DNA Repair; DNA-Binding Proteins; Female; Humans; Male; Mutation; Neurodevelopmental Disorders; Phenotype; Syndrome

Dominant mitochondrial membrane protein-associated neurodegeneration (MPAN) variants cluster within a specific C19orf12 isoform. - Rickman, Olivia J; Salter, Claire G; Gunning, Adam C; Fasham, James; Voutsina, Nikol; Leslie, Joseph S; McGavin, Lucy; Cross, Harold E; Posey, Jennifer E; Akdemir, Zeynep Coban; Jhangiani, Shalini N; Lupski, James R; et al. (Parkinsonism Relat Disord, 2021)
Mitochondria membrane protein-associated neurodegeneration (MPAN) neurodegenerative disorder is typically associated with biallelic C19orf12 variants. Here we describe a new and review candidate previous monoallelic de novo C19orf12 variants to define loss of function mutations located in the putative non-membrane spanning C19orf12 isoform as the potential basis of monoallelic MPAN.

Dominant variants in PRR12 result in unilateral or bilateral complex microphthalmia. - Reis, Linda M; Costakos, Deborah; Wheeler, Patricia G; Bardakjian, Tanya; Schneider, Adele; Fung, Simon S M; Semina, Elena V (Clin Genet, 2021)
Complex microphthalmia is characterized by small eyes with additional abnormalities that may include anterior segment dysgenesis. While many genes are known, a genetic cause is identified in only 4-30% of microphthalmia, with the lowest rate in unilateral cases. We identified four novel pathogenic loss-of-function alleles in PRR12 in families affected by complex microphthalmia and/or Peters anomaly, including two de novo, the first dominantly transmitted allele, as well as the first splicing variant. The ocular phenotypes were isolated with no additional systemic features observed in two unrelated families. Remarkably, ocular phenotypes were asymmetric in all individuals and unilateral (with structurally normal contralateral eye) in three. There are only three previously reported PRR12 variants identified in probands with intellectual disability, neuropsychiatric disorders, and iris anomalies. While some overlap with previously reported cases is seen, nonsyndromic developmental ocular anomalies are a novel phenotype for this gene. Additional phenotypic expansions included short stature and normal development/cognition, each noted in two individuals in this cohort, as well as absence of neuropsychiatric disorders in all. This study identifies new associations for PRR12 disruption in humans and presents a genetic diagnosis resulting in unilateral ocular phenotypes in a significant proportion of cases.

Dual activating FGFR1 mutations in pediatric pilomyxoid astrocytoma. - Fomchenko, Elena I; Reeves, Benjamin C; Sullivan, William; Marks, Asher M; Huttner, Anita; Kahle, Kristopher T; Erson-Omay, E Zeynep (Mol Genet Genomic Med, 2021)
BACKGROUND: Pilomyxoid astrocytomas are an aggressive subtype of astrocytoma, not graded by WHO, frequently located in hypothalamic/chiasmatic region, affecting diencephalic structures, and characterized by shorter survival and high recurrence rates. Pilomyxoid astrocytoma management remains controversial, with pathologic tissue diagnosis and relief of mass effect being the main goals of surgery while avoiding treatment-related morbidity, including vision loss, panhypopituitarism, and hypothalamic dysfunction. Chemotherapy (typically vincristine and carboplatin) in all pediatric patients and radiation therapy in pediatric patients over 5 years of age are used for treatment. METHODS: We report clinical presentation, surgical management, and whole exome sequencing results in a pediatric patient with the subtotally resected pilomyxoid astrocytoma. RESULTS: We identified two somatic activating missense mutations affecting FGFR1, including FGFR1 p.K656E and FGFR1 p.V561M. While the former is a known hotspot mutation that is both activating and transforming, the latter has been described as a gatekeeper mutation imparting resistance to FGFR inhibitors. Interestingly, both mutations were present with similar variant allele frequency within the tumor. CONCLUSION: Similar variant allele frequencies of FGFR1 p.K656E and FGFR1 p.V561M mutations in our patient's tumor suggest that these mutations may have occurred at similar time points. Use of FGFR inhibitors in addition to STAT3 or PI3K/mTOR inhibition may prove a useful strategy in targeting our patient's pilomyxoid astrocytoma.

Efficient phasing and imputation of low-coverage sequencing data using large reference panels. - Rubinacci, Simone; Ribeiro, Diogo M; Hofmeister, Robin J; Delaneau, Olivier (Nat Genet, 2021)
Low-coverage whole-genome sequencing followed by imputation has been proposed as a cost-effective genotyping approach for disease and population genetics studies. However, its competitiveness against SNP arrays is undermined because current imputation methods are computationally expensive and unable to leverage large reference panels. Here, we describe a method, GLIMPSE, for phasing and imputation of low-coverage sequencing datasets from modern reference panels. We demonstrate its remarkable performance across different coverages and human populations. GLIMPSE achieves imputation of a genome for less than US$1 in computational cost, considerably outperforming other methods and improving imputation accuracy over the full allele frequency range. As a proof of concept, we show that 1× coverage enables effective gene expression association studies and outperforms dense SNP arrays in rare variant burden tests. Overall, this study illustrates the promising potential of low-coverage imputation and suggests a paradigm shift in the design of future genomic studies.
Keywords: Genome, Human; Genotype; Humans; Likelihood Functions; Polymorphism, Single Nucleotide; Reference Standards; Sequence Analysis, DNA

Exome sequencing identifies novel missense and deletion variants in RTN4IP1 associated with optic atrophy, global developmental delay, epilepsy, ataxia, and choreoathetosis. - D'Gama, Alissa M; England, Eleina; Madden, Jill A; Shi, JiAHi; Chao, Katherine R; Wojcik, Monica H; Torres, Alcy R; Tan, Wen-Hann; Berry, Gerard T; Prabhu, Sanjay P; Agrawal, Pankaj B (Am J Med Genet A, 2021)
Inherited optic neuropathies (IONs) are neurodegenerative disorders characterized by optic atrophy with or without extraocular manifestations. Optic atrophy-10 (OPA10) is an autosomal recessive ION recently reported to be caused by mutations in RTN4IP1, which encodes reticulon 4 interacting protein 1 (RTN4IP1), a mitochondrial ubiquinol oxydo-reductase. Here we report novel compound heterozygous mutations in RTN4IP1 in a male proband with developmental delay, epilepsy, optic atrophy, ataxia, and choreoathetosis. Workup was notable for transiently elevated lactate and lactate-to-pyruvate ratio, brain magnetic resonance imaging with optic atrophy and T2 signal abnormalities, and a nondiagnostic initial genetic workup, including chromosomal microarray and mitochondrial panel testing. Exome sequencing identified a paternally inherited missense variant (c.263T>G, p.Val88Gly) predicted to be deleterious and a maternally inherited deletion encompassing RTN4IP1. To our knowledge, this is the first report of a non-single nucleotide pathogenic variant associated with OPA10. This case highlights the expanding phenotypic spectrum of OPA10, the association between "syndromic" cases and severe RTN4IP1 mutations, and the importance of nonbiased genetic testing, such as ES, to analyze multiple genes and variants types, in patients suspected of having genetic disease.

Exome sequencing reveals predominantly de novo variants in disorders with intellectual disability (ID) in the founder population of Finland. - Järvelä, Irma; Määttä, Tuomo; Acharya, Anushree; Leppälä, Juha; Jhangiani, Shalini N; Arvio, Maria; Siren, Auli; Kankuri-Tammilehto, Minna; Kokkonen, Hannaleena; Palomäki, Maarit; Varilo, Teppo; Fang, Mary; et al. (Hum Genet, 2021)
The genetics of autosomal recessive intellectual disability (ARID) has mainly been studied in consanguineous families, however, founder populations may also be of interest to study intellectual disability (ID) and the contribution of ARID. Here, we used a genotype-driven approach to study the genetic landscape of ID in the founder population of Finland. A total of 39 families with syndromic and non-syndromic ID were analyzed using exome sequencing, which revealed a variant in a known ID gene in 27 families. Notably, 75% of these variants in known ID genes were de novo or suspected de novo (64% autosomal dominant; 11% X-linked) and 25% were inherited (14% autosomal recessive; 7% X-linked; and 4% autosomal dominant). A dual molecular diagnosis was suggested in two families (5%). Via additional analysis and molecular testing, we identified three cases with an abnormal molecular karyotype, including chr21q22.12q22.2 uniparental disomy with a mosaic interstitial 2.7 Mb deletion covering DYRK1A and KCNJ6. Overall, a pathogenic or likely pathogenic variant was identified in 64% (25/39) of the families. Last, we report an alternate inheritance model for 3 known ID genes (UBA7, DDX47, DHX58) and discuss potential candidate genes for ID, including SYPL1 and ERGIC3 with homozygous founder variants and de novo variants in POLR2F and DNAH3. In summary, similar to other European populations, de novo variants were the most common variants underlying ID in the studied Finnish population, with limited contribution of ARID to ID etiology, though mainly driven by founder and potential founder variation in the latter case.

Exome-wide rare variant analysis in familial essential tremor. - Diez-Fairen, Monica; Houle, Gabrielle; Ortega-Cubero, Sara; Bandres-Ciga, Sara; Alvarez, Ignacio; Carcel, Maria; Ibañez, Laura; Fernandez, Maria Victoria; Budde, John P; Trotta, Jean-Rémi; Tonda, Raúl; Chong, Jessica X; et al. (Parkinsonism Relat Disord, 2021)
INTRODUCTION: Essential tremor (ET) is one of the most common movement disorders. Despite its high prevalence and heritability, its genetic etiology remains elusive with only a few susceptibility genes identified and poorly replicated. Our aim was to find novel candidate genes involved in ET predisposition through whole exome sequencing. METHODS: We studied eight multigenerational families (N = 40 individuals) with an autosomal-dominant inheritance using a comprehensive strategy combining whole exome sequencing followed by case-control association testing of prioritized variants in a separate cohort comprising 521 ET cases and 596 controls. We further performed gene-based burden analyses in an additional dataset comprising 789 ET patients and 770 healthy individuals to investigate whether there was an enrichment of rare deleterious variants within our candidate genes. RESULTS: Fifteen variants co-segregated with disease status in at least one of the families, among which rs749875462 in CCDC183, rs535864157 in MMP10 and rs114285050 in GPR151 showed a nominal association with ET. However, we found no significant enrichment of rare variants within these genes in cases compared with controls. Interestingly, MMP10 protein is involved in the inflammatory response to neuronal damage and has been previously associated with other neurological disorders. CONCLUSIONS: We prioritized a set of promising genes, especially MMP10, for further genetic and functional studies in ET. Our study suggests that rare deleterious coding variants that markedly increase susceptibility to ET are likely to be found in many genes. Future studies are needed to replicate and further infer biological mechanisms and potential disease causality for our identified genes.

Expanded CAG Repeats in ATXN1, ATXN2, ATXN3, and HTT in the 1000 Genomes Project. - Akçimen, Fulya; Ross, Jay P; Liao, Calwing; Spiegelman, Dan; Dion, Patrick A; Rouleau, Guy A (Mov Disord, 2021)
BACKGROUND: Spinocerebellar ataxia types 1, 2, 3 and Huntington disease are neurodegenerative disorders caused by expanded CAG repeats. METHODS: We performed an in-silico analysis of CAG repeats in ATXN1, ATXN2, ATXN3, and HTT using 30× whole-=genome sequencing data of 2504 samples from the 1000 Genomes Project. RESULTS: Seven HTT-positive, 3 ATXN2-positive, 1 ATXN3-positive, and 6 possibly ATXN1-positive samples were identified. No correlation was found between the repeat sizes of the different genes. The distribution of CAG alleles varied by ethnicity. CONCLUSION: Our results suggest that there may be asymptomatic small expanded repeats in almost 0.5% of these populations. © 2020 International Parkinson and Movement Disorder Society.
Keywords: Alleles; Ataxin-1; Ataxin-2; Ataxin-3; Humans; Huntingtin Protein; Huntington Disease; Repressor Proteins; Spinocerebellar Ataxias; Trinucleotide Repeat Expansion; Trinucleotide Repeats

Expanding the phenotype, genotype and biochemical knowledge of ALG3-CDG. - Alsharhan, Hind; Ng, Bobby G; Daniel, Earnest James Paul; Friedman, Jennifer; Pivnick, Eniko K; Al-Hashem, Amal; Faqeih, Eissa Ali; Liu, Pengfei; Engelhardt, Nicole M; Keller, Kierstin N; Chen, Jie; Mazzeo, Pamela A; et al. (J Inherit Metab Dis, 2021)
Congenital disorders of glycosylation (CDGs) are a continuously expanding group of monogenic disorders of glycoprotein and glycolipid biosynthesis that cause multisystem diseases. Individuals with ALG3-CDG frequently exhibit severe neurological involvement (epilepsy, microcephaly, and hypotonia), ocular anomalies, dysmorphic features, skeletal anomalies, and feeding difficulties. We present 10 unreported individuals diagnosed with ALG3-CDG based on molecular and biochemical testing with 11 novel variants in ALG3, bringing the total to 40 reported individuals. In addition to the typical multisystem disease seen in ALG3-CDG, we expand the symptomatology of ALG3-CDG to now include endocrine abnormalities, neural tube defects, mild aortic root dilatation, immunodeficiency, and renal anomalies. N-glycan analyses of these individuals showed combined deficiencies of hybrid glycans and glycan extension beyond Man GlcNAc consistent with their truncated lipid-linked precursor oligosaccharides. This spectrum of N-glycan changes is unique to ALG3-CDG. These expanded features of ALG3-CDG facilitate diagnosis and suggest that optimal management should include baseline endocrine, renal, cardiac, and immunological evaluation at the time of diagnosis and with ongoing monitoring.

Familial thrombocytopenia due to a complex structural variant resulting in a WAC-ANKRD26 fusion transcript. - Wahlster, Lara; Verboon, Jeffrey M; Ludwig, Leif S; Black, Susan C; Luo, Wendy; Garg, Kopal; Voit, Richard A; Collins, Ryan L; Garimella, Kiran; Costello, Maura; Chao, Katherine R; Goodrich, Julia K; et al. (J Exp Med, 2021)
Advances in genome sequencing have resulted in the identification of the causes for numerous rare diseases. However, many cases remain unsolved with standard molecular analyses. We describe a family presenting with a phenotype resembling inherited thrombocytopenia 2 (THC2). THC2 is generally caused by single nucleotide variants that prevent silencing of ANKRD26 expression during hematopoietic differentiation. Short-read whole-exome and genome sequencing approaches were unable to identify a causal variant in this family. Using long-read whole-genome sequencing, a large complex structural variant involving a paired-duplication inversion was identified. Through functional studies, we show that this structural variant results in a pathogenic gain-of-function WAC-ANKRD26 fusion transcript. Our findings illustrate how complex structural variants that may be missed by conventional genome sequencing approaches can cause human disease.

Further delineation of van den Ende-Gupta syndrome: Genetic heterogeneity and overlap with congenital heart defects and skeletal malformations syndrome. - Hildebrandt, Clara C; Patel, Nisha; GrAHm, John M; Bamshad, Michael; Nickerson, Deborah A; White, Janson J; Marvin, Colby T; Miller, Danny E; Grand, Katheryn L; Sanchez-Lara, Pedro A; Schweitzer, Daniela; Al-Zaidan, Hamad I; et al. (Am J Med Genet A, 2021)
Van den Ende-Gupta syndrome (VDEGS) is a rare autosomal recessive condition characterized by distinctive facial and skeletal features, and in most affected persons, by biallelic pathogenic variants in SCARF2. We review the type and frequency of the clinical features in 36 reported individuals with features of VDEGS, 15 (42%) of whom had known pathogenic variants in SCARF2, 6 (16%) with negative SCARF2 testing, and 15 (42%) not tested. We also report three new individuals with pathogenic variants in SCARF2 and clinical features of VDEGS. Of the six persons without known pathogenic variants in SCARF2, three remain unsolved despite extensive genetic testing. Three were found to have pathogenic ABL1 variants using whole exome sequencing (WES) or whole genome sequencing (WGS). Their phenotype was consistent with the congenital heart disease and skeletal malformations syndrome (CHDSKM), which has been associated with ABL1 variants. Of the three unsolved cases, two were brothers who underwent WGS and targeted long-range sequencing of both SCARF2 and ABL1, and the third person who underwent WES and RNA sequencing for SCARF2. Because these affected individuals with classical features of VDEGS lacked a detectable pathogenic SCARF2 variant, genetic heterogeneity is likely. Our study shows the importance of performing genetic testing on individuals with the VDEGS "phenotype," either as a targeted gene analysis (SCARF2, ABL1) or WES/WGS. Additionally, individuals with the combination of arachnodactyly and blepharophimosis should undergo echocardiography while awaiting results of molecular testing due to the overlapping physical features of VDEGS and CHDSKM.

Generation of Monogenic Candidate Genes for Human Nephrotic Syndrome Using 3 Independent Approaches. - Klämbt, Verena; Mao, Youying; Schneider, Ronen; Buerger, Florian; Shamseldin, Hanan; Onuchic-Whitford, Ana C; Deutsch, Konstantin; Kitzler, Thomas M; Nakayama, Makiko; Majmundar, Amar J; Mann, Nina; Hugo, Hannah; et al. (Kidney Int Rep, 2021)
Introduction: Steroid-resistant nephrotic syndrome (SRNS) is the second most common cause of chronic kidney disease during childhood. Identification of 63 monogenic human genes has delineated 12 distinct pathogenic pathways. Methods: Here, we generated 2 independent sets of nephrotic syndrome (NS) candidate genes to augment the discovery of additional monogenic causes based on whole-exome sequencing (WES) data from 1382 families with NS. Results: We first identified 63 known monogenic causes of NS in mice from public databases and scientific publications, and 12 of these genes overlapped with the 63 known human monogenic SRNS genes. Second, we used a set of 64 genes that are regulated by the transcription factor Wilms tumor 1 (WT1), which causes SRNS if mutated. Thirteen of these WT1-regulated genes overlapped with human or murine NS genes. Finally, we overlapped these lists of murine and WT1 candidate genes with our list of 120 candidate genes generated from WES in 1382 NS families, to identify novel candidate genes for monogenic human SRNS. Using this approach, we identified 7 overlapping genes, of which 3 genes were shared by all datasets, including . We show that loss-of-function of leads to decreased CDC42 activity and reduced podocyte migration rate, both of which are rescued by overexpression of wild-type complementary DNA (cDNA), but not by cDNA representing the patient mutation. Conclusion: Thus, we identified 3 novel candidate genes for human SRNS using 3 independent, nonoverlapping hypotheses, and generated functional evidence for as a novel potential monogenic cause of NS.

Genetic and non-genetic factors affecting the expression of COVID-19-relevant genes in the large airway epithelium. - Kasela, Silva; Ortega, Victor E; Martorella, Molly; Garudadri, Suresh; Nguyen, Jenna; Ampleford, Elizabeth; Pasanen, Anu; Nerella, Srilaxmi; Buschur, Kristina L; Barjaktarevic, Igor Z; Barr, R Graham; Bleecker, Eugene R; et al. (Genome Med, 2021)
BACKGROUND: The large airway epithelial barrier provides one of the first lines of defense against respiratory viruses, including SARS-CoV-2 that causes COVID-19. Substantial inter-individual variability in individual disease courses is hypothesized to be partially mediated by the differential regulation of the genes that interact with the SARS-CoV-2 virus or are involved in the subsequent host response. Here, we comprehensively investigated non-genetic and genetic factors influencing COVID-19-relevant bronchial epithelial gene expression. METHODS: We analyzed RNA-sequencing data from bronchial epithelial brushings obtained from uninfected individuals. We related ACE2 gene expression to host and environmental factors in the SPIROMICS cohort of smokers with and without chronic obstructive pulmonary disease (COPD) and replicated these associations in two asthma cohorts, SARP and MAST. To identify airway biology beyond ACE2 binding that may contribute to increased susceptibility, we used gene set enrichment analyses to determine if gene expression changes indicative of a suppressed airway immune response observed early in SARS-CoV-2 infection are also observed in association with host factors. To identify host genetic variants affecting COVID-19 susceptibility in SPIROMICS, we performed expression quantitative trait (eQTL) mapping and investigated the phenotypic associations of the eQTL variants. RESULTS: We found that ACE2 expression was higher in relation to active smoking, obesity, and hypertension that are known risk factors of COVID-19 severity, while an association with interferon-related inflammation was driven by the truncated, non-binding ACE2 isoform. We discovered that expression patterns of a suppressed airway immune response to early SARS-CoV-2 infection, compared to other viruses, are similar to patterns associated with obesity, hypertension, and cardiovascular disease, which may thus contribute to a COVID-19-susceptible airway environment. eQTL mapping identified regulatory variants for genes implicated in COVID-19, some of which had pheWAS evidence for their potential role in respiratory infections. CONCLUSIONS: These data provide evidence that clinically relevant variation in the expression of COVID-19-related genes is associated with host factors, environmental exposures, and likely host genetic variation.
Keywords: Adult; Aged; Aged, 80 and over; Angiotensin-Converting Enzyme 2; Asthma; Bronchi; Cardiovascular Diseases; COVID-19; Gene Expression; Genetic Variation; Humans; Middle Aged; Obesity; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; Respiratory Mucosa; Risk Factors; SARS-CoV-2; Smoking

Genetic Predictor to Identify Individuals With High Lipoprotein(a) Concentrations. - Dron, Jacqueline S; Wang, Minxian; Patel, Aniruddh P; Kartoun, Uri; Ng, Kenney; Hegele, Robert A; Khera, Amit V (Circ Genom Precis Med, 2021)

Genetic profiles of 103,106 individuals in the Taiwan Biobank provide insights into the health and history of Han Chinese. - Wei, Chun-Yu; Yang, Jenn-Hwai; Yeh, Erh-Chan; Tsai, Ming-Fang; Kao, Hsiao-Jung; Lo, Chen-Zen; Chang, Lung-Pao; Lin, Wan-Jia; Hsieh, Feng-Jen; Belsare, Saurabh; Bhaskar, Anand; Su, Ming-Wei; et al. (NPJ Genom Med, 2021)
Personalized medical care focuses on prediction of disease risk and response to medications. To build the risk models, access to both large-scale genomic resources and human genetic studies is required. The Taiwan Biobank (TWB) has generated high-coverage, whole-genome sequencing data from 1492 individuals and genome-wide SNP data from 103,106 individuals of Han Chinese ancestry using custom SNP arrays. Principal components analysis of the genotyping data showed that the full range of Han Chinese genetic variation was found in the cohort. The arrays also include thousands of known functional variants, allowing for simultaneous ascertainment of Mendelian disease-causing mutations and variants that affect drug metabolism. We found that 21.2% of the population are mutation carriers of autosomal recessive diseases, 3.1% have mutations in cancer-predisposing genes, and 87.3% carry variants that affect drug response. We highlight how TWB data provide insight into both population history and disease burden, while showing how widespread genetic testing can be used to improve clinical care.

Germline mutation in : a heterogeneous, multi-systemic developmental disorder characterized by transcriptional dysregulation. - Hansen, Adam W; Arora, Payal; Khayat, Michael M; Smith, Leah J; Lewis, Andrea M; Rossetti, Linda Z; Jayaseelan, Joy; Cristian, Ingrid; Haynes, Devon; DiTroia, Stephanie; Meeks, Naomi; Delgado, Mauricio R; et al. (HGG Adv, 2021)
germline variation in was recently reported to associate with a neurodevelopmental disorder. We report twelve individuals harboring putatively pathogenic or inherited variants in , detail their phenotypes, and map all known variants to the domain structure of and crystal structure of RNA polymerase II. Affected individuals were ascertained from a local data lake, pediatric genetics clinic, and an online community of families of affected individuals. These include six affected by missense variants (including one previously reported individual), four clinical laboratory samples affected by missense variation with unknown inheritance-with yeast functional assays further supporting altered function-one affected by a in-frame deletion, and one affected by a C-terminal frameshift variant inherited from a largely asymptomatic mother. Recurrently observed phenotypes include ataxia, joint hypermobility, short stature, skin abnormalities, congenital cardiac abnormalities, immune system abnormalities, hip dysplasia, and short Achilles tendons. We report a significantly higher occurrence of epilepsy (8/12, 66.7%) than previously reported (3/15, 20%) (p value = 0.014196; chi-square test) and a lower occurrence of hypotonia (8/12, 66.7%) than previously reported (14/15, 93.3%) (p value = 0.076309). -related developmental disorders likely represent a spectrum of related, multi-systemic developmental disorders, driven by distinct mechanisms, converging at a single locus.

Germline SAMD9L truncation variants trigger global translational repression. - Allenspach, Eric J; Soveg, Frank; Finn, Laura S; So, Lomon; Gorman, Jacquelyn A; Rosen, Aaron B I; Skoda-Smith, Suzanne; Wheeler, Marsha M; Barrow, Kaitlyn A; Rich, Lucille M; Debley, Jason S; Bamshad, Michael J; et al. (J Exp Med, 2021)
SAMD9L is an interferon-induced tumor suppressor implicated in a spectrum of multisystem disorders, including risk for myeloid malignancies and immune deficiency. We identified a heterozygous de novo frameshift variant in SAMD9L in an infant with B cell aplasia and clinical autoinflammatory features who died from respiratory failure with chronic rhinovirus infection. Autopsy demonstrated absent bone marrow and peripheral B cells as well as selective loss of Langerhans and Purkinje cells. The frameshift variant led to expression of a truncated protein with interferon treatment. This protein exhibited a gain-of-function phenotype, resulting in interference in global protein synthesis via inhibition of translational elongation. Using a mutational scan, we identified a region within SAMD9L where stop-gain variants trigger a similar translational arrest. SAMD9L variants that globally suppress translation had no effect or increased mRNA transcription. The complex-reported phenotype likely reflects lineage-dominant sensitivities to this translation block. Taken together, our findings indicate that interferon-triggered SAMD9L gain-of-function variants globally suppress translation.

GIMAP5 maintains liver endothelial cell homeostasis and prevents portal hypertension. - Drzewiecki, Kaela; Choi, Jungmin; Brancale, Joseph; Leney-Greene, Michael A; Sari, Sinan; Dalgiç, Buket; Ünlüsoy Aksu, Aysel; Evirgen Şahin, Gülseren; Ozen, Ahmet; Baris, Safa; Karakoc-Aydiner, Elif; Jain, Dhanpat; et al. (J Exp Med, 2021)
Portal hypertension is a major contributor to decompensation and death from liver disease, a global health problem. Here, we demonstrate homozygous damaging mutations in GIMAP5, a small organellar GTPase, in four families with unexplained portal hypertension. We show that GIMAP5 is expressed in hepatic endothelial cells and that its loss in both humans and mice results in capillarization of liver sinusoidal endothelial cells (LSECs); this effect is also seen when GIMAP5 is selectively deleted in endothelial cells. Single-cell RNA-sequencing analysis in a GIMAP5-deficient mouse model reveals replacement of LSECs with capillarized endothelial cells, a reduction of macrovascular hepatic endothelial cells, and places GIMAP5 upstream of GATA4, a transcription factor required for LSEC specification. Thus, GIMAP5 is a critical regulator of liver endothelial cell homeostasis and, when absent, produces portal hypertension. These findings provide new insight into the pathogenesis of portal hypertension, a major contributor to morbidity and mortality from liver disease.

Haplotype-resolved diverse human genomes and integrated analysis of structural variation. - Ebert, Peter; Audano, Peter A; Zhu, Qihui; Rodriguez-Martin, Bernardo; Porubsky, David; Bonder, Marc Jan; Sulovari, Arvis; Ebler, Jana; Zhou, Weichen; Serra Mari, Rebecca; Yilmaz, Feyza; Zhao, Xuefang; et al. (Science, 2021)
Long-read and strand-specific sequencing technologies together facilitate the de novo assembly of high-quality haplotype-resolved human genomes without parent-child trio data. We present 64 assembled haplotypes from 32 diverse human genomes. These highly contiguous haplotype assemblies (average minimum contig length needed to cover 50% of the genome: 26 million base pairs) integrate all forms of genetic variation, even across complex loci. We identified 107,590 structural variants (SVs), of which 68% were not discovered with short-read sequencing, and 278 SV hotspots (spanning megabases of gene-rich sequence). We characterized 130 of the most active mobile element source elements and found that 63% of all SVs arise through homology-mediated mechanisms. This resource enables reliable graph-based genotyping from short reads of up to 50,340 SVs, resulting in the identification of 1526 expression quantitative trait loci as well as SV candidates for adaptive selection within the human population.
Keywords: Female; Genetic Variation; Genome, Human; Genotype; Haplotypes; High-Throughput Nucleotide Sequencing; Humans; INDEL Mutation; Interspersed Repetitive Sequences; Male; Population Groups; Quantitative Trait Loci; Retroelements; Sequence Analysis, DNA; Sequence Inversion; Whole Genome Sequencing

Identification of homozygous mutations for hearing loss. - Dianatpour, Mehdi; Smith, Emily; Hashemi, Seyed Basir; Farazifard, Mohammad A; Nezafat, Navid; Razban, Vahid; Mani, Arya (Gene, 2021)
BACKGROUND: Hearing loss is the most common sensory disorder worldwide, affecting about 1 out of every 1000 newborns. The disease has major genetic components, and can be inherited as a single gene disorder either in autosomal dominant or recessive fashions. Due to the high rate of consanguineous unions, Iran has one of the highest prevalence of autosomal recessive nonsyndromic deafness (ARNSD) in the world. METHODS: We carried out a genetic screening of ten Iranian kindreds with more than one offspring affected by ARNSD caused by consanguineous unions. Sanger sequencing and whole exome sequencing together with in silico 3D structure modeling and protein stability prediction were used to identify the underlying disease causing genes. CONCLUSION: We identified the causes of deafness in all 10 kindred. In six kindreds homozygous mutations were identified in GJB2 gene by Sanger sequencing. By using whole exome sequencing (WES), a homozygous missense mutation was identified in ESRRB gene as the first ever reported disease gene in Iran. Also two novel homozygous frameshift and missense mutations were identified in MYO15A gene and one previously reported mutation in TMC1 gene in three independent kindred. Our study shows the efficacy of WES for unraveling new pathogenic mutations in ARNSD patients and expands the spectrum of genes contributing to ARNSD in the Iranian population. The findings of our study can facilitate future genetic screening of patients with ARNSD , early screening and optimal design of novel therapeutics.
Keywords: Connexin 26; Consanguinity; Female; Frameshift Mutation; Genetic Predisposition to Disease; Hearing Loss; Homozygote; Humans; Iran; Male; Membrane Proteins; Models, Molecular; Mutation, Missense; Myosins; Pedigree; Protein Stability; Receptors, Estrogen; Whole Exome Sequencing

Identification of Required Host Factors for SARS-CoV-2 Infection in Human Cells. - Daniloski, Zharko; Jordan, Tristan X; Wessels, Hans-Hermann; Hoagland, Daisy A; Kasela, Silva; Legut, Mateusz; Maniatis, Silas; Mimitou, Eleni P; Lu, Lu; Geller, Evan; Danziger, Oded; Rosenberg, Brad R; et al. (Cell, 2021)
To better understand host-virus genetic dependencies and find potential therapeutic targets for COVID-19, we performed a genome-scale CRISPR loss-of-function screen to identify host factors required for SARS-CoV-2 viral infection of human alveolar epithelial cells. Top-ranked genes cluster into distinct pathways, including the vacuolar ATPase proton pump, Retromer, and Commander complexes. We validate these gene targets using several orthogonal methods such as CRISPR knockout, RNA interference knockdown, and small-molecule inhibitors. Using single-cell RNA-sequencing, we identify shared transcriptional changes in cholesterol biosynthesis upon loss of top-ranked genes. In addition, given the key role of the ACE2 receptor in the early stages of viral entry, we show that loss of RAB7A reduces viral entry by sequestering the ACE2 receptor inside cells. Overall, this work provides a genome-scale, quantitative resource of the impact of the loss of each host gene on fitness/response to viral infection.
Keywords: A549 Cells; Alveolar Epithelial Cells; Angiotensin-Converting Enzyme 2; Biosynthetic Pathways; Cholesterol; Clustered Regularly Interspaced Short Palindromic Repeats; COVID-19; Endosomes; Gene Expression Profiling; Gene Knockdown Techniques; Gene Knockout Techniques; Genome-Wide Association Study; Host-Pathogen Interactions; Humans; rab GTP-Binding Proteins; RNA Interference; SARS-CoV-2; Single-Cell Analysis; Viral Load

IFN-α2a Therapy in Two Patients with Inborn Errors of TLR3 and IRF3 Infected with SARS-CoV-2. - Lévy, Romain; Bastard, Paul; Lanternier, Fanny; Lecuit, Marc; Zhang, Shen-Ying; Casanova, Jean-Laurent (J Clin Immunol, 2021)
Keywords: Adult; COVID-19; Female; Humans; Interferon Regulatory Factor-3; Interferon Type I; Interferon-alpha; Polyethylene Glycols; Primary Immunodeficiency Diseases; Recombinant Proteins; SARS-CoV-2; Toll-Like Receptor 3; Treatment Outcome

Increased Burden of Rare Sequence Variants in GnRH-Associated Genes in Women With Hypothalamic Amenorrhea. - Delaney, Angela; Burkholder, Adam B; Lavender, Christopher A; Plummer, Lacey; Mericq, Veronica; Merino, Paulina M; Quinton, Richard; Lewis, Katie L; Meader, Brooke N; Albano, Alessandro; Shaw, Natalie D; Welt, Corrine K; et al. (J Clin Endocrinol Metab, 2021)
CONTEXT: Functional hypothalamic amenorrhea (HA) is a common, acquired form of hypogonadotropic hypogonadism that occurs in the setting of energy deficits and/or stress. Variability in individual susceptibility to these stressors, HA heritability, and previous identification of several rare sequence variants (RSVs) in genes associated with the rare disorder, isolated hypogonadotropic hypogonadism (IHH), in individuals with HA suggest a possible genetic contribution to HA susceptibility. OBJECTIVE: We sought to determine whether the burden of RSVs in IHH-related genes is greater in women with HA than controls. DESIGN: We compared patients with HA to control women. SETTING: The study was conducted at secondary referral centers. PATIENTS AND OTHER PARTICIPANTS: Women with HA (n = 106) and control women (ClinSeq study; n = 468). INTERVENTIONS: We performed exome sequencing in all patients and controls. MAIN OUTCOME MEASURE(S): The frequency of RSVs in 53 IHH-associated genes was determined using rare variant burden and association tests. RESULTS: RSVs were overrepresented in women with HA compared with controls (P = .007). Seventy-eight heterozygous RSVs in 33 genes were identified in 58 women with HA (36.8% of alleles) compared to 255 RSVs in 41 genes among 200 control women (27.2%). CONCLUSIONS: Women with HA are enriched for RSVs in genes that cause IHH, suggesting that variation in genes associated with gonadotropin-releasing hormone neuronal ontogeny and function may be a major determinant of individual susceptibility to developing HA in the face of diet, exercise, and/or stress.

Inhibition of HECT E3 ligases as potential therapy for COVID-19. - Novelli, Giuseppe; Liu, Jing; Biancolella, Michela; Alonzi, Tonino; Novelli, Antonio; Patten, J J; Cocciadiferro, Dario; Agolini, Emanuele; Colona, Vito Luigi; Rizzacasa, Barbara; Giannini, Rosalinda; Bigio, Benedetta; et al. (Cell Death Dis, 2021)
SARS-CoV-2 is responsible for the ongoing world-wide pandemic which has already taken more than two million lives. Effective treatments are urgently needed. The enzymatic activity of the HECT-E3 ligase family members has been implicated in the cell egression phase of deadly RNA viruses such as Ebola through direct interaction of its VP40 Protein. Here we report that HECT-E3 ligase family members such as NEDD4 and WWP1 interact with and ubiquitylate the SARS-CoV-2 Spike protein. Furthermore, we find that HECT family members are overexpressed in primary samples derived from COVID-19 infected patients and COVID-19 mouse models. Importantly, rare germline activating variants in the NEDD4 and WWP1 genes are associated with severe COVID-19 cases. Critically, I3C, a natural NEDD4 and WWP1 inhibitor from Brassicaceae, displays potent antiviral effects and inhibits viral egression. In conclusion, we identify the HECT family members of E3 ligases as likely novel biomarkers for COVID-19, as well as new potential targets of therapeutic strategy easily testable in clinical trials in view of the established well-tolerated nature of the Brassicaceae natural compounds.
Keywords: Adult; Aged; Animals; Antiviral Agents; Chlorocebus aethiops; COVID-19; Endosomal Sorting Complexes Required for Transport; Female; Humans; Indoles; Male; Mice; Mice, Inbred BALB C; Middle Aged; Nedd4 Ubiquitin Protein Ligases; SARS-CoV-2; Spike Glycoprotein, Coronavirus; Ubiquitin-Protein Ligases; Ubiquitination; Vero Cells

Longitudinal single-cell epitope and RNA-sequencing reveals the immunological impact of type 1 interferon autoantibodies in critical COVID-19. - van der Wijst, Monique G P; Vazquez, Sara E; Hartoularos, George C; Bastard, Paul; Grant, Tianna; Bueno, Raymund; Lee, David S; Greenland, John R; Sun, Yang; Perez, Richard; Ogorodnikov, Anton; Ward, Alyssa; et al. (bioRxiv, 2021)
Type I interferon (IFN-I) neutralizing autoantibodies have been found in some critical COVID-19 patients; however, their prevalence and longitudinal dynamics across the disease severity scale, and functional effects on circulating leukocytes remain unknown. Here, in 284 COVID-19 patients, we found IFN-I autoantibodies in 19% of critical, 6% of severe and none of the moderate cases. Longitudinal profiling of over 600,000 peripheral blood mononuclear cells using multiplexed single-cell epitope and transcriptome sequencing from 54 COVID-19 patients, 15 non-COVID-19 patients and 11 non-hospitalized healthy controls, revealed a lack of IFN-I stimulated gene (ISG-I) response in myeloid cells from critical cases, including those producing anti-IFN-I autoantibodies. Moreover, surface protein analysis showed an inverse correlation of the inhibitory receptor LAIR-1 with ISG-I expression response early in the disease course. This aberrant ISG-I response in critical patients with and without IFN-I autoantibodies, supports a unifying model for disease pathogenesis involving ISG-I suppression via convergent mechanisms.

Loss of function mutations in GEMIN5 cause a neurodevelopmental disorder. - Kour, Sukhleen; Rajan, Deepa S; Fortuna, Tyler R; Anderson, Eric N; Ward, Caroline; Lee, Youngha; Lee, Sangmoon; Shin, Yong Beom; Chae, Jong-Hee; Choi, Murim; Siquier, Karine; Cantagrel, Vincent; et al. (Nat Commun, 2021)
GEMIN5, an RNA-binding protein is essential for assembly of the survival motor neuron (SMN) protein complex and facilitates the formation of small nuclear ribonucleoproteins (snRNPs), the building blocks of spliceosomes. Here, we have identified 30 affected individuals from 22 unrelated families presenting with developmental delay, hypotonia, and cerebellar ataxia harboring biallelic variants in the GEMIN5 gene. Mutations in GEMIN5 perturb the subcellular distribution, stability, and expression of GEMIN5 protein and its interacting partners in patient iPSC-derived neurons, suggesting a potential loss-of-function mechanism. GEMIN5 mutations result in disruption of snRNP complex assembly formation in patient iPSC neurons. Furthermore, knock down of rigor mortis, the fly homolog of human GEMIN5, leads to developmental defects, motor dysfunction, and a reduced lifespan. Interestingly, we observed that GEMIN5 variants disrupt a distinct set of transcripts and pathways as compared to SMA patient neurons, suggesting different molecular pathomechanisms. These findings collectively provide evidence that pathogenic variants in GEMIN5 perturb physiological functions and result in a neurodevelopmental delay and ataxia syndrome.
Keywords: Alleles; Amino Acid Sequence; Animals; Child, Preschool; Developmental Disabilities; Drosophila; Female; Gene Expression Regulation, Developmental; Gene Knockdown Techniques; Gene Ontology; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Loss of Function Mutation; Male; Muscle Hypotonia; Myoclonic Cerebellar Dyssynergia; Neurodevelopmental Disorders; Neurons; Pedigree; Polymorphism, Single Nucleotide; Ribonucleoproteins, Small Nuclear; Rigor Mortis; RNA-Seq; SMN Complex Proteins

MED27 Variants Cause Developmental Delay, Dystonia, and Cerebellar Hypoplasia. - Meng, Linyan; Isohanni, Pirjo; Shao, Yunru; GrAHm, Brett H; Hickey, Scott E; Brooks, Stephanie; Suomalainen, Anu; Joset, Pascal; Steindl, Katharina; Rauch, Anita; Hackenberg, Annette; High, Frances A; et al. (Ann Neurol, 2021)
The Mediator multiprotein complex functions as a regulator of RNA polymerase II-catalyzed gene transcription. In this study, exome sequencing detected biallelic putative disease-causing variants in MED27, encoding Mediator complex subunit 27, in 16 patients from 11 families with a novel neurodevelopmental syndrome. Patient phenotypes are highly homogeneous, including global developmental delay, intellectual disability, axial hypotonia with distal spasticity, dystonic movements, and cerebellar hypoplasia. Seizures and cataracts were noted in severely affected individuals. Identification of multiple patients with biallelic MED27 variants supports the critical role of MED27 in normal human neural development, particularly for the cerebellum. ANN NEUROL 2021;89:828-833.
Keywords: Adolescent; Adult; Amino Acid Sequence; Cataract; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Dystonia; Epilepsy; Genetic Variation; Humans; Infant; Mediator Complex; Nervous System Malformations; Phenotype; Whole Exome Sequencing

METAP1 mutation is a novel candidate for autosomal recessive intellectual disability. - Çağlayan, Ahmet Okay; Aktar, Fesih; Bilguvar, Kaya; Baranoski, Jacob F; Akgümüş, Gözde Tuğce; Harmanci, Akdes Serin; Erson-Omay, Emine Zeynep; Yasuno, Katsuhito; Caksen, Huseyin; Günel, Murat (J Hum Genet, 2021)
Intellectual disability (ID) is a genetic and clinically heterogeneous common disease and underlying molecular pathogenesis can frequently not be identified by whole-exome/genome testing. Here, we report four siblings born to a consanguineous union who presented with intellectual disability and discuss the METAP1 pathway as a novel etiology of ID. Genomic analyses demonstrated that patients harbor a novel homozygous nonsense mutation in the gene METAP1. METAP1 codes for methionine aminopeptidase 1 (MetAP1) which oversees the co-translational excision of the first methionine remnants in eukaryotes. The loss-of-function mutations to this gene may result in a defect in the translation of many essential proteins within a cell. Improper neuronal function resulting from this loss of essential proteins could lead to neurologic impairment and ID.

Multiomic analysis elucidates Complex I deficiency caused by a deep intronic variant in NDUFB10. - Helman, Guy; Compton, Alison G; Hock, Daniella H; Walkiewicz, Marzena; Brett, Gemma R; Pais, Lynn; Tan, Tiong Y; De Paoli-Iseppi, Ricardo; Clark, Michael B; Christodoulou, John; White, Susan M; Thorburn, David R; et al. (Hum Mutat, 2021)
The diagnosis of Mendelian disorders following uninformative exome and genome sequencing remains a challenging and often unmet need. Following uninformative exome and genome sequencing of a family quartet including two siblings with suspected mitochondrial disorder, RNA sequencing (RNAseq) was pursued in one sibling. Long-read amplicon sequencing was used to determine and quantify transcript structure. Immunoblotting studies and quantitative proteomics were performed to demonstrate functional impact. Differential expression analysis of RNAseq data identified significantly decreased expression of the mitochondrial OXPHOS Complex I subunit NDUFB10 associated with a cryptic exon in intron 1 of NDUFB10, that included an in-frame stop codon. The cryptic exon contained a rare intronic variant that was homozygous in both affected siblings. Immunoblot and quantitative proteomic analysis of fibroblasts revealed decreased abundance of Complex I subunits, providing evidence of isolated Complex I deficiency. Through multiomic analysis we present data implicating a deep intronic variant in NDUFB10 as the cause of mitochondrial disease in two individuals, providing further support of the gene-disease association. This study highlights the importance of transcriptomic and proteomic analyses as complementary diagnostic tools in patients undergoing genome-wide diagnostic evaluation.

Mutations in Spliceosomal Genes PPIL1 and PRP17 Cause Neurodegenerative Pontocerebellar Hypoplasia with Microcephaly. - Chai, Guoliang; Webb, Alice; Li, Chen; Antaki, Danny; Lee, Sangmoon; Breuss, Martin W; Lang, Nhi; Stanley, Valentina; Anzenberg, Paula; Yang, Xiaoxu; Marshall, Trevor; Gaffney, Patrick; et al. (Neuron, 2021)
Autosomal-recessive cerebellar hypoplasia and ataxia constitute a group of heterogeneous brain disorders caused by disruption of several fundamental cellular processes. Here, we identified 10 families showing a neurodegenerative condition involving pontocerebellar hypoplasia with microcephaly (PCHM). Patients harbored biallelic mutations in genes encoding the spliceosome components Peptidyl-Prolyl Isomerase Like-1 (PPIL1) or Pre-RNA Processing-17 (PRP17). Mouse knockouts of either gene were lethal in early embryogenesis, whereas PPIL1 patient mutation knockin mice showed neuron-specific apoptosis. Loss of either protein affected splicing integrity, predominantly affecting short and high GC-content introns and genes involved in brain disorders. PPIL1 and PRP17 form an active isomerase-substrate interaction, but we found that isomerase activity is not critical for function. Thus, we establish disrupted splicing integrity and "major spliceosome-opathies" as a new mechanism underlying PCHM and neurodegeneration and uncover a non-enzymatic function of a spliceosomal proline isomerase.
Keywords: Amino Acid Sequence; Animals; Cell Cycle Proteins; Cerebellar Diseases; Cohort Studies; Female; Gene Knockout Techniques; HEK293 Cells; Heredodegenerative Disorders, Nervous System; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microcephaly; Mutation; Pedigree; Peptidylprolyl Isomerase; Protein Structure, Secondary; Protein Structure, Tertiary; RNA Splicing Factors; Spliceosomes

Mutations in transcription factor CP2-like 1 may cause a novel syndrome with distal renal tubulopathy in humans. - Klämbt, Verena; Werth, Max; Onuchic-Whitford, Ana C; Getwan, Maike; Kitzler, Thomas M; Buerger, Florian; Mao, Youying; Deutsch, Konstantin; Mann, Nina; Majmundar, Amar J; Kaminski, Michael M; Shen, Tian; et al. (Nephrol Dial Transplant, 2021)
BACKGROUND: An underlying monogenic cause of early-onset chronic kidney disease (CKD) can be detected in ∼20% of individuals. For many etiologies of CKD manifesting before 25 years of age, >200 monogenic causative genes have been identified to date, leading to the elucidation of mechanisms of renal pathogenesis. METHODS: In 51 families with echogenic kidneys and CKD, we performed whole-exome sequencing to identify novel monogenic causes of CKD. RESULTS: We discovered a homozygous truncating mutation in the transcription factor gene transcription factor CP2-like 1 (TFCP2L1) in an Arabic patient of consanguineous descent. The patient developed CKD by the age of 2 months and had episodes of severe hypochloremic, hyponatremic and hypokalemic alkalosis, seizures, developmental delay and hypotonia together with cataracts. We found that TFCP2L1 was localized throughout kidney development particularly in the distal nephron. Interestingly, TFCP2L1 induced the growth and development of renal tubules from rat mesenchymal cells. Conversely, the deletion of TFCP2L1 in mice was previously shown to lead to reduced expression of renal cell markers including ion transporters and cell identity proteins expressed in different segments of the distal nephron. TFCP2L1 localized to the nucleus in HEK293T cells only upon coexpression with its paralog upstream-binding protein 1 (UBP1). A TFCP2L1 mutant complementary DNA (cDNA) clone that represented the patient's mutation failed to form homo- and heterodimers with UBP1, an essential step for its transcriptional activity. CONCLUSION: Here, we identified a loss-of-function TFCP2L1 mutation as a potential novel cause of CKD in childhood accompanied by a salt-losing tubulopathy.
Keywords: Animals; Child; DNA-Binding Proteins; Epithelial-Mesenchymal Transition; Female; HEK293 Cells; Humans; Kidney Diseases; Mice; Mice, Knockout; Mutation; Rats; Repressor Proteins; Single-Cell Analysis; Transcription Factors; Whole Exome Sequencing

Neurodevelopmental disorder in an Egyptian family with a biallelic ALKBH8 variant. - Saad, Ahmed K; Marafi, Dana; Mitani, Tadahiro; Du, Haowei; Rafat, Karima; Fatih, Jawid M; Jhangiani, Shalini N; Coban-Akdemir, Zeynep; Gibbs, Richard A; Pehlivan, Davut; Hunter, Jill V; Posey, Jennifer E; et al. (Am J Med Genet A, 2021)
Alkylated DNA repair protein AlkB homolog 8 (ALKBH8) is a member of the AlkB family of dioxygenases. ALKBH8 is a methyltransferase of the highly variable wobble nucleoside position in the anticodon loop of tRNA and thus plays a critical role in tRNA modification by preserving codon recognition and preventing errors in amino acid incorporation during translation. Moreover, its activity catalyzes uridine modifications that are proposed to be critical for accurate protein translation. Previously, two distinct homozygous truncating variants in the final exon of ALKBH8 were described in two unrelated large Saudi Arabian kindreds with intellectual developmental disorder and autosomal recessive 71 (MRT71) syndrome (MIM# 618504). Here, we report a third family-of Egyptian descent-harboring a novel homozygous frame-shift variant in the last exon of ALKBH8. Two affected siblings in this family exhibit global developmental delay and intellectual disability as shared characteristic features of MRT71 syndrome, and we further characterize their observed dysmorphic features and brain MRI findings. This description of a third family with a truncating ALKBH8 variant from a distinct population broadens the phenotypic and genotypic spectrum of MRT71 syndrome, affirms that perturbations in tRNA biogenesis can contribute to neurogenetic disease traits, and firmly establishes ALKBH8 as a novel neurodevelopmental disease gene.

Neutralizing Autoantibodies to Type I IFNs in >10% of Patients with Severe COVID-19 Pneumonia Hospitalized in Madrid, Spain. - Troya, Jesús; Bastard, Paul; Planas-Serra, Laura; Ryan, Pablo; Ruiz, Montse; de Carranza, María; Torres, Juan; Martínez, Amalia; Abel, Laurent; Casanova, Jean-Laurent; Pujol, Aurora (J Clin Immunol, 2021)
BACKGROUND: In a recent study, autoantibodies neutralizing type I interferons (IFNs) were present in at least 10% of cases of critical COVID-19 pneumonia. These autoantibodies neutralized most type I IFNs but rarely IFN-beta. OBJECTIVES: We aimed to define the prevalence of autoantibodies neutralizing type I IFN in a cohort of patients with severe COVID-19 pneumonia treated with IFN-beta-1b during hospitalization and to analyze their impact on various clinical variables and outcomes. METHODS: We analyzed stored serum/plasma samples and clinical data of COVID-19 patients treated subcutaneously with IFN-beta-1b from March to May 2020, at the Infanta Leonor University Hospital in Madrid, Spain. RESULTS: The cohort comprised 47 COVID-19 patients with severe pneumonia, 16 of whom (34%) had a critical progression requiring ICU admission. The median age was 71 years, with 28 men (58.6%). Type I IFN-alpha- and omega-neutralizing autoantibodies were found in 5 of 47 patients with severe pneumonia or critical disease (10.6%), while they were not found in any of the 118 asymptomatic controls (p = 0.0016). The autoantibodies did not neutralize IFN-beta. No demographic, comorbidity, or clinical differences were seen between individuals with or without autoantibodies. We found a significant correlation between the presence of neutralizing autoantibodies and higher C-reactive protein levels (p = 5.10e) and lower lymphocyte counts (p = 1.80e). No significant association with response to IFN-beta-1b therapy (p = 0.34) was found. Survival analysis suggested that neutralizing autoantibodies may increase the risk of death (4/5, 80% vs 12/42, 28.5%). CONCLUSION: Autoantibodies neutralizing type I IFN underlie severe/critical COVID-19 stages in at least 10% of cases, correlate with increased C-RP and lower lymphocyte counts, and confer a trend towards increased risk of death. Subcutaneous IFN-beta treatment of hospitalized patients did not seem to improve clinical outcome. Studies of earlier, ambulatory IFN-beta treatment are warranted.

Neutralizing Autoantibodies to Type I Interferons in COVID-19 Convalescent Donor Plasma. - Vazquez, Sara E; Bastard, Paul; Kelly, Kathleen; Gervais, Adrian; Norris, Philip J; Dumont, Larry J; Casanova, Jean-Laurent; Anderson, Mark S; Derisi, Joseph L (J Clin Immunol, 2021)

NMIHBA results from hypomorphic PRUNE1 variants that lack short-chain exopolyphosphatase activity. - Nistala, Harikiran; Dronzek, John; Gonzaga-Jauregui, Claudia; Chim, Shek Man; Rajamani, Saathyaki; Nuwayhid, Samer; Delgado, Dennis; Burke, Elizabeth; Karaca, Ender; Franklin, Matthew C; Sarangapani, Prasad; Podgorski, Michael; et al. (Hum Mol Genet, 2021)
Neurodevelopmental disorder with microcephaly, hypotonia and variable brain anomalies (NMIHBA) is an autosomal recessive neurodevelopmental and neurodegenerative disorder characterized by global developmental delay and severe intellectual disability. Microcephaly, progressive cortical atrophy, cerebellar hypoplasia and delayed myelination are neurological hallmarks in affected individuals. NMIHBA is caused by biallelic variants in PRUNE1 encoding prune exopolyphosphatase 1. We provide in-depth clinical description of two affected siblings harboring compound heterozygous variant alleles, c.383G > A (p.Arg128Gln), c.520G > T (p.Gly174*) in PRUNE1. To gain insights into disease biology, we biochemically characterized missense variants within the conserved N-terminal aspartic acid-histidine-histidine (DHH) motif and provide evidence that they result in the destabilization of protein structure and/or loss of exopolyphosphatase activity. Genetic ablation of Prune1 results in midgestational lethality in mice, associated with perturbations to embryonic growth and vascular development. Our findings suggest that NMIHBA results from hypomorphic variant alleles in humans and underscore the potential key role of PRUNE1 exopolyphoshatase activity in neurodevelopment.

A novel homozygous SLC13A5 whole-gene deletion generated by Alu/Alu-mediated rearrangement in an Iraqi family with epileptic encephalopathy. - Duan, Ruizhi; Saadi, Nebal Waill; Grochowski, Christopher M; Bhadila, Ghalia; Faridoun, Afnan; Mitani, Tadahiro; Du, Haowei; Fatih, Jawid M; Jhangiani, Shalini N; Akdemir, Zeynep C; Gibbs, Richard A; Pehlivan, Davut; et al. (Am J Med Genet A, 2021)
Biallelic loss-of-function (LoF) of SLC13A5 (solute carrier family 13, member 5) induced deficiency in sodium/citrate transporter (NaCT) causes autosomal recessive developmental epileptic encephalopathy 25 with hypoplastic amelogenesis imperfecta (DEE25; MIM #615905). Many pathogenic SLC13A5 single nucleotide variants (SNVs) and small indels have been described; however, no cases with copy number variants (CNVs) have been sufficiently investigated. We describe a consanguineous Iraqi family harboring an 88.5 kb homozygous deletion including SLC13A5 in Chr17p13.1. The three affected male siblings exhibit neonatal-onset epilepsy with fever-sensitivity, recurrent status epilepticus, global developmental delay/intellectual disability (GDD/ID), and other variable neurological findings as shared phenotypical features of DEE25. Two of the three affected subjects exhibit hypoplastic amelogenesis imperfecta (AI), while the proband shows no evidence of dental abnormalities or AI at 2 years of age with apparently unaffected primary dentition. Characterization of the genomic architecture at this locus revealed evidence for genomic instability generated by an Alu/Alu-mediated rearrangement; confirmed by break-point junction Sanger sequencing. This multiplex family from a distinct population elucidates the phenotypic consequence of complete LoF of SLC13A5 and illustrates the importance of read-depth-based CNV detection in comprehensive exome sequencing analysis to solve cases that otherwise remain molecularly unsolved.

Novel variants in TUBA1A cause congenital fibrosis of the extraocular muscles with or without malformations of cortical brain development. - Jurgens, Julie A; Barry, Brenda J; Lemire, Gabrielle; Chan, Wai-Man; Whitman, Mary C; Shaaban, Sherin; Robson, Caroline D; MacKinnon, Sarah; England, Eleina M; McMillan, Hugh J; Kelly, Christopher; Pratt, Brandon M; et al. (Eur J Hum Genet, 2021)
Variants in multiple tubulin genes have been implicated in neurodevelopmental disorders, including malformations of cortical development (MCD) and congenital fibrosis of the extraocular muscles (CFEOM). Distinct missense variants in the beta-tubulin encoding genes TUBB3 and TUBB2B cause MCD, CFEOM, or both, suggesting substitution-specific mechanisms. Variants in the alpha tubulin-encoding gene TUBA1A have been associated with MCD, but not with CFEOM. Using exome sequencing (ES) and genome sequencing (GS), we identified 3 unrelated probands with CFEOM who harbored novel heterozygous TUBA1A missense variants c.1216C>G, p.(His406Asp); c.467G>A, p.(Arg156His); and c.1193T>G, p.(Met398Arg). MRI revealed small oculomotor-innervated muscles and asymmetrical caudate heads and lateral ventricles with or without corpus callosal thinning. Two of the three probands had MCD. Mutated amino acid residues localize either to the longitudinal interface at which α and β tubulins heterodimerize (Met398, His406) or to the lateral interface at which tubulin protofilaments interact (Arg156), and His406 interacts with the motor domain of kinesin-1. This series of individuals supports TUBA1A variants as a cause of CFEOM and expands our knowledge of tubulinopathies.

Optimized sample selection for cost-efficient long-read population sequencing. - Ranallo-Benavidez, T Rhyker; Lemmon, Zachary; Soyk, Sebastian; Aganezov, Sergey; Salerno, William J; McCoy, Rajiv C; Lippman, Zachary B; Schatz, Michael C; Sedlazeck, Fritz J (Genome Res, 2021)
An increasingly important scenario in population genetics is when a large cohort has been genotyped using a low-resolution approach (e.g., microarrays, exome capture, short-read WGS), from which a few individuals are resequenced using a more comprehensive approach, especially long-read sequencing. The subset of individuals selected should ensure that the captured genetic diversity is fully representative and includes variants across all subpopulations. For example, human variation has historically focused on individuals with European ancestry, but this represents a small fraction of the overall diversity. Addressing this, SVCollector identifies the optimal subset of individuals for resequencing by analyzing population-level VCF files from low-resolution genotyping studies. It then computes a ranked list of samples that maximizes the total number of variants present within a subset of a given size. To solve this optimization problem, SVCollector implements a fast, greedy heuristic and an exact algorithm using integer linear programming. We apply SVCollector on simulated data, 2504 human genomes from the 1000 Genomes Project, and 3024 genomes from the 3000 Rice Genomes Project and show the rankings it computes are more representative than alternative naive strategies. When selecting an optimal subset of 100 samples in these cohorts, SVCollector identifies individuals from every subpopulation, whereas naive methods yield an unbalanced selection. Finally, we show the number of variants present in cohorts selected using this approach follows a power-law distribution that is naturally related to the population genetic concept of the allele frequency spectrum, allowing us to estimate the diversity present with increasing numbers of samples.

Pathogenic deep intronic MTM1 variant activates a pseudo-exon encoding a nonsense codon resulting in severe X-linked myotubular myopathy. - Bryen, Samantha J; Oates, Emily C; Evesson, Frances J; Lu, Jessica K; Waddell, Leigh B; Joshi, Himanshu; Ryan, Monique M; Cummings, Beryl B; McLean, Catriona A; MacArthur, Daniel G; Kornberg, Andrew J; Cooper, Sandra T (Eur J Hum Genet, 2021)
X-linked myotubular myopathy (XLMTM) is a severe congenital myopathy characterised by generalised weakness and respiratory insufficiency. XLMTM is associated with pathogenic variants in MTM1; a gene encoding the lipid phosphatase myotubularin. Whole genome sequencing (WGS) of an exome-negative male proband with severe hypotonia, respiratory insufficiency and centralised nuclei on muscle biopsy identified a deep intronic MTM1 variant NG_008199.1(NM_000252.2):c.1468-577A>G, which strengthened a cryptic 5' splice site (A>G substitution at the +5 position). Muscle RNA sequencing was non-diagnostic due to low read depth. Reverse transcription PCR (RT-PCR) of muscle RNA confirmed the c.1468-577A>G variant activates inclusion of a pseudo-exon encoding a premature stop codon into all detected MTM1 transcripts. Western blot analysis establishes deficiency of myotubularin protein, consistent with the severe XLMTM phenotype. We expand the genotypic spectrum of XLMTM and highlight benefits of screening non-coding regions of MTM1 in male probands with phenotypically concordant XLMTM who remain undiagnosed following exome sequencing.

Pathogenic variants in , a chromatin remodeler, cause a range of syndromic neurodevelopmental features. - Li, Dong; Wang, Qin; Gong, Naihua N; Kurolap, Alina; Feldman, Hagit Baris; Boy, Nikolas; Brugger, Melanie; Grand, Katheryn; McWalter, Kirsty; Guillen Sacoto, Maria J; Wakeling, Emma; Hurst, Jane; et al. (Sci Adv, 2021)
Intellectual disability encompasses a wide spectrum of neurodevelopmental disorders, with many linked genetic loci. However, the underlying molecular mechanism for more than 50% of the patients remains elusive. We describe pathogenic variants in , encoding the ATPase motor of the ISWI chromatin remodeler, as a cause of a previously unidentified neurodevelopmental disorder, identifying 12 individuals with de novo or dominantly segregating rare heterozygous variants. Accompanying phenotypes include mild developmental delay, frequent postnatal short stature and microcephaly, and recurrent dysmorphic features. Loss of function of the SMARCA5 ortholog led to smaller body size, reduced sensory dendrite complexity, and tiling defects in larvae. In adult flies, Iswi neural knockdown caused decreased brain size, aberrant mushroom body morphology, and abnormal locomotor function. loss of function was rescued by wild-type but not mutant SMARCA5. Our results demonstrate that pathogenic variants cause a neurodevelopmental syndrome with mild facial dysmorphia.

Perturbations of genes essential for Müllerian duct and Wölffian duct development in Mayer-Rokitansky-Küster-Hauser syndrome. - Chen, Na; Zhao, Sen; Jolly, Angad; Wang, Lianlei; Pan, Hongxin; Yuan, Jian; Chen, Shaoke; Koch, André; Ma, Congcong; Tian, Weijie; Jia, Ziqi; Kang, Jia; et al. (Am J Hum Genet, 2021)
Mayer-Rokitansky-Küster-Hauser syndrome (MRKHS) is associated with congenital absence of the uterus, cervix, and the upper part of the vagina; it is a sex-limited trait. Disrupted development of the Müllerian ducts (MD)/Wölffian ducts (WD) through multifactorial mechanisms has been proposed to underlie MRKHS. In this study, exome sequencing (ES) was performed on a Chinese discovery cohort (442 affected subjects and 941 female control subjects) and a replication MRKHS cohort (150 affected subjects of mixed ethnicity from North America, South America, and Europe). Phenotypic follow-up of the female reproductive system was performed on an additional cohort of PAX8-associated congenital hypothyroidism (CH) (n = 5, Chinese). By analyzing 19 candidate genes essential for MD/WD development, we identified 12 likely gene-disrupting (LGD) variants in 7 genes: PAX8 (n = 4), BMP4 (n = 2), BMP7 (n = 2), TBX6 (n = 1), HOXA10 (n = 1), EMX2 (n = 1), and WNT9B (n = 1), while LGD variants in these genes were not detected in control samples (p = 1.27E-06). Interestingly, a sex-limited penetrance with paternal inheritance was observed in multiple families. One additional PAX8 LGD variant from the replication cohort and two missense variants from both cohorts were revealed to cause loss-of-function of the protein. From the PAX8-associated CH cohort, we identified one individual presenting a syndromic condition characterized by CH and MRKHS (CH-MRKHS). Our study demonstrates the comprehensive utilization of knowledge from developmental biology toward elucidating genetic perturbations, i.e., rare pathogenic alleles involving the same loci, contributing to human birth defects.
Keywords: 46, XX Disorders of Sex Development; Adult; Bone Morphogenetic Protein 4; Bone Morphogenetic Protein 7; Codon, Nonsense; Congenital Abnormalities; Female; Genetic Association Studies; Genetic Pleiotropy; Homeobox A10 Proteins; Homeodomain Proteins; Humans; Mullerian Ducts; Mutation; Paternal Inheritance; PAX8 Transcription Factor; Penetrance; T-Box Domain Proteins; Transcription Factors; Wnt Proteins; Wolffian Ducts

Phenotypic and protein localization heterogeneity associated with AHDC1 pathogenic protein-truncating alleles in Xia-Gibbs syndrome. - Khayat, Michael M; Li, He; Chander, Varuna; Hu, Jianhong; Hansen, Adam W; Li, Shoudong; Traynelis, Josh; Shen, Hua; Weissenberger, George; Stossi, Fabio; Johnson, Hannah L; Lupski, James R; et al. (Hum Mutat, 2021)
Xia-Gibbs syndrome (XGS) is a rare Mendelian disease typically caused by de novo stop-gain or frameshift mutations in the AT-hook DNA binding motif containing 1 (AHDC1) gene. Patients usually present in early infancy with hypotonia and developmental delay and later exhibit intellectual disability (ID). The overall presentation is variable, however, and the emerging clinical picture is still evolving. A detailed phenotypic analysis of 34 XGS individuals revealed five core phenotypes (delayed motor milestones, speech delay, low muscle tone, ID, and hypotonia) in more than 80% of individuals and an additional 12 features that occurred more variably. Seizures and scoliosis were more frequently associated with truncations that arise before the midpoint of the protein although the occurrence of most features could not be predicted by the mutation position. Transient expression of wild type and different patient truncated AHDC1 protein forms in human cell lines revealed abnormal patterns of nuclear localization including a diffuse distribution of a short truncated form and nucleolar aggregation in mid-protein truncated forms. Overall, both the occurrence of variable phenotypes and the different distribution of the expressed protein reflect the heterogeneity of this syndrome.

Phylogenetic history of patrilineages rare in northern and eastern Europe from large-scale re-sequencing of human Y-chromosomes. - Ilumäe, Anne-Mai; Post, Helen; Flores, Rodrigo; Karmin, Monika; Sahakyan, Hovhannes; Mondal, Mayukh; Montinaro, Francesco; Saag, Lauri; Bormans, Concetta; Sanchez, Luisa Fernanda; Ameur, Adam; Gyllensten, Ulf; et al. (Eur J Hum Genet, 2021)
The most frequent Y-chromosomal (chrY) haplogroups in northern and eastern Europe (NEE) are well-known and thoroughly characterised. Yet a considerable number of men in every population carry rare paternal lineages with estimated frequencies around 5%. So far, limited sample-sizes and insufficient resolution of genotyping have obstructed a truly comprehensive look into the variety of rare paternal lineages segregating within populations and potential signals of population history that such lineages might convey. Here we harness the power of massive re-sequencing of human Y chromosomes to identify previously unknown population-specific clusters among rare paternal lineages in NEE. We construct dated phylogenies for haplogroups E2-M215, J2-M172, G-M201 and Q-M242 on the basis of 421 (of them 282 novel) high-coverage chrY sequences collected from large-scale databases focusing on populations of NEE. Within these otherwise rare haplogroups we disclose lineages that began to radiate ~1-3 thousand years ago in Estonia and Sweden and reveal male phylogenetic patterns testifying of comparatively recent local demographic expansions. Conversely, haplogroup Q lineages bear evidence of ancient Siberian influence lingering in the modern paternal gene pool of northern Europe. We assess the possible direction of influx of ancestral carriers for some of these male lineages. In addition, we demonstrate the congruency of paternal haplogroup composition of our dataset with two independent population-based cohorts from Estonia and Sweden.

Plasma Exchange to Rescue Patients with Autoantibodies Against Type I Interferons and Life-Threatening COVID-19 Pneumonia. - de Prost, Nicolas; Bastard, Paul; Arrestier, Romain; Fourati, Slim; Mahévas, Mathieu; Burrel, Sonia; Dorgham, Karim; Gorochov, Guy; Tandjaoui-Lambiotte, Yacine; Azzaoui, Iname; Fernandes, Ignacio; Combes, Alain; et al. (J Clin Immunol, 2021)
PURPOSE: To report four cases of life-threatening COVID-19 pneumonia in patients with high blood concentrations of neutralizing autoantibodies against type I interferons (IFNs), who were treated with plasma exchange (PE) as a rescue therapy. METHODS: Prospective case series, which included patients, diagnosed with RT-PCR-confirmed SARS-CoV-2 infection and positive autoantibodies against type I IFNs in two French intensive care units (ICUs) between October 8 and November 14, 2020. Six critically ill COVID-19 patients with no anti-IFN antibodies were used as controls. Anti-IFN autoantibodies and IFN concentrations, together with the levels of anti-SARS-CoV-2 antibodies, were measured sequentially in serum. Viral load was determined in the upper and lower respiratory tract. Patients were followed during hospital stay. RESULTS: Three men and one woman were included. Three of the patients had four PE sessions each, while another had three PE sessions. PE decreased the concentrations of autoantibodies against type I IFN in all four patients, whereas anti-SARS-CoV-2 antibody levels remained stable. Autoantibodies against type I IFN levels were high in tracheal aspirates of one patient and decreased after three PE sessions. By contrast, anti-IFN autoantibodies were not detected in tracheal aspirates from five control patients without detectable anti-IFN autoantibodies in serum. During PE, serum IFN-α levels slightly increased in three out of four patients, and upper respiratory tract viral load decreased in all patients. All patients were alive at day 28 of ICU admission. Two patients eventually died in the ICU, while the two survivors were discharged from the ICU at days 50 and 66. CONCLUSIONS: PE efficiently removes autoantibodies against type I IFNs, including those detected in tracheal aspirates, without affecting anti-SARS-CoV-2 antibody levels, in patients with life-threatening COVID-19 pneumonia. The clinical benefit of PE in patients with autoantibodies against type I IFNs should be tested in a larger study.
Keywords: Adult; Aged; Autoantibodies; COVID-19; Female; Humans; Interferon Type I; Male; Plasma Exchange; Prospective Studies; SARS-CoV-2

POLRMT mutations impair mitochondrial transcription causing neurological disease. - Oláhová, Monika; Peter, Bradley; Szilagyi, Zsolt; Diaz-Maldonado, Hector; Singh, Meenakshi; Sommerville, Ewen W; Blakely, Emma L; Collier, Jack J; Hoberg, Emily; Stránecký, Viktor; Hartmannová, Hana; Bleyer, Anthony J; et al. (Nat Commun, 2021)
While >300 disease-causing variants have been identified in the mitochondrial DNA (mtDNA) polymerase γ, no mitochondrial phenotypes have been associated with POLRMT, the RNA polymerase responsible for transcription of the mitochondrial genome. Here, we characterise the clinical and molecular nature of POLRMT variants in eight individuals from seven unrelated families. Patients present with global developmental delay, hypotonia, short stature, and speech/intellectual disability in childhood; one subject displayed an indolent progressive external ophthalmoplegia phenotype. Massive parallel sequencing of all subjects identifies recessive and dominant variants in the POLRMT gene. Patient fibroblasts have a defect in mitochondrial mRNA synthesis, but no mtDNA deletions or copy number abnormalities. The in vitro characterisation of the recombinant POLRMT mutants reveals variable, but deleterious effects on mitochondrial transcription. Together, our in vivo and in vitro functional studies of POLRMT variants establish defective mitochondrial transcription as an important disease mechanism.
Keywords: Adolescent; Adult; Child; DNA, Mitochondrial; DNA-Directed RNA Polymerases; Female; Fibroblasts; Humans; Infant; Male; Mitochondria; Mutation; Nervous System Diseases; Oxidative Phosphorylation; Pedigree; Protein Domains; Protein Subunits; RNA, Messenger; Transcription, Genetic; Young Adult

Preexisting autoantibodies to type I IFNs underlie critical COVID-19 pneumonia in patients with APS-1. - Bastard, Paul; Orlova, Elizaveta; Sozaeva, Leila; Lévy, Romain; James, Alyssa; Schmitt, Monica M; Ochoa, Sebastian; Kareva, Maria; Rodina, Yulia; Gervais, Adrian; Le Voyer, Tom; Rosain, Jérémie; et al. (J Exp Med, 2021)
Patients with biallelic loss-of-function variants of AIRE suffer from autoimmune polyendocrine syndrome type-1 (APS-1) and produce a broad range of autoantibodies (auto-Abs), including circulating auto-Abs neutralizing most type I interferons (IFNs). These auto-Abs were recently reported to account for at least 10% of cases of life-threatening COVID-19 pneumonia in the general population. We report 22 APS-1 patients from 21 kindreds in seven countries, aged between 8 and 48 yr and infected with SARS-CoV-2 since February 2020. The 21 patients tested had auto-Abs neutralizing IFN-α subtypes and/or IFN-ω; one had anti-IFN-β and another anti-IFN-ε, but none had anti-IFN-κ. Strikingly, 19 patients (86%) were hospitalized for COVID-19 pneumonia, including 15 (68%) admitted to an intensive care unit, 11 (50%) who required mechanical ventilation, and four (18%) who died. Ambulatory disease in three patients (14%) was possibly accounted for by prior or early specific interventions. Preexisting auto-Abs neutralizing type I IFNs in APS-1 patients confer a very high risk of life-threatening COVID-19 pneumonia at any age.
Keywords: Adolescent; Adult; Autoantibodies; Child; COVID-19; Female; Humans; Interferon Type I; Male; Middle Aged; Pneumonia; Polyendocrinopathies, Autoimmune; SARS-CoV-2; Young Adult

Rapid response to the alpha-1 adrenergic agent phenylephrine in the perioperative period is impacted by genomics and ancestry. - Wenric, Stephane; Jeff, Janina M; Joseph, Thomas; Yee, Muh-Ching; Belbin, Gillian M; Owusu Obeng, Aniwaa; Ellis, Stephen B; Bottinger, Erwin P; Gottesman, Omri; Levin, Matthew A; Kenny, Eimear E (Pharmacogenomics J, 2021)
The emergence of genomic data in biobanks and health systems offers new ways to derive medically important phenotypes, including acute phenotypes occurring during inpatient clinical care. Here we study the genetic underpinnings of the rapid response to phenylephrine, an α1-adrenergic receptor agonist commonly used to treat hypotension during anesthesia and surgery. We quantified this response by extracting blood pressure (BP) measurements 5 min before and after the administration of phenylephrine. Based on this derived phenotype, we show that systematic differences exist between self-reported ancestry groups: European-Americans (EA; n = 1387) have a significantly higher systolic response to phenylephrine than African-Americans (AA; n = 1217) and Hispanic/Latinos (HA; n = 1713) (31.3% increase, p value < 6e-08 and 22.9% increase, p value < 5e-05 respectively), after adjusting for genetic ancestry, demographics, and relevant clinical covariates. We performed a genome-wide association study to investigate genetic factors underlying individual differences in this derived phenotype. We discovered genome-wide significant association signals in loci and genes previously associated with BP measured in ambulatory settings, and a general enrichment of association in these genes. Finally, we discovered two low frequency variants, present at ~1% in EAs and AAs, respectively, where patients carrying one copy of these variants show no phenylephrine response. This work demonstrates our ability to derive a quantitative phenotype suited for comparative statistics and genome-wide association studies from dense clinical and physiological measures captured for managing patients during surgery. We identify genetic variants underlying non response to phenylephrine, with implications for preemptive pharmacogenomic screening to improve safety during surgery.

A relatively common homozygous TRAPPC4 splicing variant is associated with an early-infantile neurodegenerative syndrome. - Ghosh, Shereen G; Scala, Marcello; Beetz, Christian; Helman, Guy; Stanley, Valentina; Yang, Xiaoxu; Breuss, Martin W; Mazaheri, Neda; Selim, Laila; Hadipour, Fatemeh; Pais, Lynn; Stutterd, Chloe A; et al. (Eur J Hum Genet, 2021)
Trafficking protein particle (TRAPP) complexes, which include the TRAPPC4 protein, regulate membrane trafficking between lipid organelles in a process termed vesicular tethering. TRAPPC4 was recently implicated in a recessive neurodevelopmental condition in four unrelated families due to a shared c.454+3A>G splice variant. Here, we report 23 patients from 17 independent families with an early-infantile-onset neurodegenerative presentation, where we also identified the homozygous variant hg38:11:119020256 A>G (NM_016146.5:c.454+3A>G) in TRAPPC4 through exome or genome sequencing. No other clinically relevant TRAPPC4 variants were identified among any of over 10,000 patients with neurodevelopmental conditions. We found the carrier frequency of TRAPPC4 c.454+3A>G was 2.4-5.4 per 10,000 healthy individuals. Affected individuals with the homozygous TRAPPC4 c.454+3A>G variant showed profound psychomotor delay, developmental regression, early-onset epilepsy, microcephaly and progressive spastic tetraplegia. Based upon RNA sequencing, the variant resulted in partial exon 3 skipping and generation of an aberrant transcript owing to use of a downstream cryptic splice donor site, predicting a premature stop codon and nonsense mediated decay. These data confirm the pathogenicity of the TRAPPC4 c.454+3A>G variant, and refine the clinical presentation of TRAPPC4-related encephalopathy.

Resolution of sclerotic lesions of dysosteosclerosis due to biallelic SLC29A3 variant in a Turkish girl. - Uludağ Alkaya, Dilek; Akpınar, Evren; Bilguvar, Kaya; Tuysuz, Beyhan (Am J Med Genet A, 2021)
Dysosteosclerosis is a group of sclerosing bone dysplasia characterized by short stature, increased bone fragility, osteosclerosis, and platyspondyly. It is a genetically heterogeneous disorder caused by biallelic mutations in the SLC29A3, TNFRSF11A, TCIRG1, and CSF1R genes. To date, four dysosteosclerosis patients with SLC29A3 mutations have been reported. Here, we report biallelic SLC29A3 (c.303_320dupCTACTTTGAGAGCTACCT) variant in a three-year-old girl. She had large anterior fontanelle, fracture history, short stature, camptodactyly, elbow contracture, and melanocytic nevus. Initial skeletal radiographs revealed platyspondyly, dense vertebral endplates (sandwich appearance of the vertebral bodies), diffuse sclerosis of the peripheral side of the pelvic bones, sclerosis of metaphysis and diaphysis of the long bones, metaphyseal widening, and diaphyseal cortical thickening. Mild sclerosis was also present in the skull base, maxilla, rib, scapula, and phalanges. Notably, we observed that sandwich vertebrae appearance significantly resolved and sclerosis of ribs, scapula, pelvis, and long bone metaphysis regressed over a 2.5-year period. However, platyspondyly, metaphyseal widening, and diaphyseal cortical thickening persisted. In conclusion, this study demonstrates spontaneous resolution of osteosclerosis, which was not described previously in patients with dysosteosclerosis.

Rho-GTPase Activating Protein myosin MYO9A identified as a novel candidate gene for monogenic focal segmental glomerulosclerosis. - Li, Qi; Gulati, Ashima; Lemaire, Mathieu; Nottoli, Timothy; Bale, Allen; Tufro, Alda (Kidney Int, 2021)
Focal segmental glomerulosclerosis (FSGS) is a podocytopathy leading to kidney failure, whose molecular cause frequently remains unresolved. Here, we describe a rare MYO9A loss of function nonsense heterozygous mutation (p.Arg701) as a possible contributor to disease in a sibling pair with familial FSGS/proteinuria. MYO9A variants of uncertain significance were identified by whole exome sequencing in a cohort of 94 biopsy proven patients with FSGS. MYO9A is an unconventional myosin with a Rho-GAP domain that controls epithelial cell junction assembly, crosslinks and bundles actin and deactivates the small GTPase protein encoded by the RHOA gene. RhoA activity is associated with cytoskeleton regulation of actin stress fiber formation and actomyosin contractility. Myo9A was detected in mouse and human podocytes in vitro and in vivo. Knockin mice carrying the p.Arg701MYO9A (Myo9A) generated by gene editing developed proteinuria, podocyte effacement and FSGS. Kidneys and podocytes from Myo9A mutant mice revealed Myo9A haploinsufficiency, increased RhoA activity, decreased Myo9A-actin-calmodulin interaction, impaired podocyte attachment and migration. Our results indicate that Myo9A is a novel component of the podocyte cytoskeletal apparatus that regulates RhoA activity and podocyte function. Thus, Myo9A knock-in mice recapitulate the proband FSGS phenotype, demonstrate that p.R701X Myo9A is an FSGS-causing mutation in mice and suggest that heterozygous loss-of-function MYO9A mutations may cause a novel form of human autosomal dominant FSGS. Hence, identification of MYO9A pathogenic variants in additional individuals with familial or sporadic FSGS is needed to ascertain the gene contribution to disease.

SARS-CoV-2 induces human plasmacytoid predendritic cell diversification via UNC93B and IRAK4. - Onodi, Fanny; Bonnet-Madin, Lucie; Meertens, Laurent; Karpf, Léa; Poirot, Justine; Zhang, Shen-Ying; Picard, Capucine; Puel, Anne; Jouanguy, Emmanuelle; Zhang, Qian; Le Goff, Jérôme; Molina, Jean-Michel; et al. (J Exp Med, 2021)
Several studies have analyzed antiviral immune pathways in late-stage severe COVID-19. However, the initial steps of SARS-CoV-2 antiviral immunity are poorly understood. Here we have isolated primary SARS-CoV-2 viral strains and studied their interaction with human plasmacytoid predendritic cells (pDCs), a key player in antiviral immunity. We show that pDCs are not productively infected by SARS-CoV-2. However, they efficiently diversified into activated P1-, P2-, and P3-pDC effector subsets in response to viral stimulation. They expressed CD80, CD86, CCR7, and OX40 ligand at levels similar to influenza virus-induced activation. They rapidly produced high levels of interferon-α, interferon-λ1, IL-6, IP-10, and IL-8. All major aspects of SARS-CoV-2-induced pDC activation were inhibited by hydroxychloroquine. Mechanistically, SARS-CoV-2-induced pDC activation critically depended on IRAK4 and UNC93B1, as established using pDC from genetically deficient patients. Overall, our data indicate that human pDC are efficiently activated by SARS-CoV-2 particles and may thus contribute to type I IFN-dependent immunity against SARS-CoV-2 infection.
Keywords: Biomarkers; Cell Plasticity; COVID-19; Cytokines; Dendritic Cells; Host-Pathogen Interactions; Humans; Hydroxychloroquine; Immunomodulation; Immunophenotyping; Inflammation Mediators; Interferon Type I; Interferons; Interleukin-1 Receptor-Associated Kinases; Membrane Transport Proteins; SARS-CoV-2

SARS-CoV-2 induces human plasmacytoid pre-dendritic cell diversification via UNC93B and IRAK4. - Onodi, Fanny; Bonnet-Madin, Lucie; Meertens, Laurent; Karpf, Léa; Poirot, Justine; Zhang, Shen-Ying; Picard, Capucine; Puel, Anne; Jouanguy, Emmanuelle; Zhang, Qian; Le Goff, Jérôme; Molina, Jean-Michel; et al. (bioRxiv, 2021)
Several studies have analyzed antiviral immune pathways in late-stage severe COVID-19. However, the initial steps of SARS-CoV-2 antiviral immunity are poorly understood. Here, we have isolated primary SARS-CoV-2 viral strains, and studied their interaction with human plasmacytoid pre-dendritic cells (pDC), a key player in antiviral immunity. We show that pDC are not productively infected by SARS-CoV-2. However, they efficiently diversified into activated P1-, P2-, and P3-pDC effector subsets in response to viral stimulation. They expressed CD80, CD86, CCR7, and OX40 ligand at levels similar to influenza virus-induced activation. They rapidly produced high levels of interferon-α, interferon-λ1, IL-6, IP-10, and IL-8. All major aspects of SARS-CoV-2-induced pDC activation were inhibited by hydroxychloroquine. Mechanistically, SARS-CoV-2-induced pDC activation critically depended on IRAK4 and UNC93B1, as established using pDC from genetically deficient patients. Overall, our data indicate that human pDC are efficiently activated by SARS-CoV-2 particles and may thus contribute to type I IFN-dependent immunity against SARS-CoV-2 infection.

SARS-CoV-2-related MIS-C: A key to the viral and genetic causes of Kawasaki disease? - Sancho-Shimizu, Vanessa; Brodin, Petter; Cobat, Aurelie; Biggs, Catherine M; Toubiana, Julie; Lucas, Carrie L; Henrickson, Sarah E; Belot, Alexandre; Tangye, Stuart G; Milner, Joshua D; Levin, Michael; Abel, Laurent; et al. (J Exp Med, 2021)
Multisystem inflammatory syndrome in children (MIS-C) emerged in April 2020 in communities with high COVID-19 rates. This new condition is heterogenous but resembles Kawasaki disease (KD), a well-known but poorly understood and clinically heterogenous pediatric inflammatory condition for which weak associations have been found with a myriad of viral illnesses. Epidemiological data clearly indicate that SARS-CoV-2 is the trigger for MIS-C, which typically occurs about 1 mo after infection. These findings support the hypothesis of viral triggers for the various forms of classic KD. We further suggest that rare inborn errors of immunity (IEIs) altering the immune response to SARS-CoV-2 may underlie the pathogenesis of MIS-C in some children. The discovery of monogenic IEIs underlying MIS-C would shed light on its pathogenesis, paving the way for a new genetic approach to classic KD, revisited as a heterogeneous collection of IEIs to viruses.
Keywords: Biomarkers; Child; COVID-19; Cytokines; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inflammation; Inflammation Mediators; Lymphohistiocytosis, Hemophagocytic; Models, Biological; Mucocutaneous Lymph Node Syndrome; Pandemics; SARS-CoV-2; Systemic Inflammatory Response Syndrome

SPEN haploinsufficiency causes a neurodevelopmental disorder overlapping proximal 1p36 deletion syndrome with an episignature of X chromosomes in females. - Radio, Francesca Clementina; Pang, Kaifang; Ciolfi, Andrea; Levy, Michael A; Hernandez-Garcia, Andres; Pedace, Lucia; Pantaleoni, Francesca; Liu, Zhandong; de Boer, Elke; Jackson, Adam; Bruselles, Alessandro; McConkey, Haley; et al. (Am J Hum Genet, 2021)
Deletion 1p36 (del1p36) syndrome is the most common human disorder resulting from a terminal autosomal deletion. This condition is molecularly and clinically heterogeneous. Deletions involving two non-overlapping regions, known as the distal (telomeric) and proximal (centromeric) critical regions, are sufficient to cause the majority of the recurrent clinical features, although with different facial features and dysmorphisms. SPEN encodes a transcriptional repressor commonly deleted in proximal del1p36 syndrome and is located centromeric to the proximal 1p36 critical region. Here, we used clinical data from 34 individuals with truncating variants in SPEN to define a neurodevelopmental disorder presenting with features that overlap considerably with those of proximal del1p36 syndrome. The clinical profile of this disease includes developmental delay/intellectual disability, autism spectrum disorder, anxiety, aggressive behavior, attention deficit disorder, hypotonia, brain and spine anomalies, congenital heart defects, high/narrow palate, facial dysmorphisms, and obesity/increased BMI, especially in females. SPEN also emerges as a relevant gene for del1p36 syndrome by co-expression analyses. Finally, we show that haploinsufficiency of SPEN is associated with a distinctive DNA methylation episignature of the X chromosome in affected females, providing further evidence of a specific contribution of the protein to the epigenetic control of this chromosome, and a paradigm of an X chromosome-specific episignature that classifies syndromic traits. We conclude that SPEN is required for multiple developmental processes and SPEN haploinsufficiency is a major contributor to a disorder associated with deletions centromeric to the previously established 1p36 critical regions.
Keywords: Adolescent; Autism Spectrum Disorder; Child; Child, Preschool; Chromosome Deletion; Chromosome Disorders; Chromosomes, Human, Pair 1; Chromosomes, Human, X; DNA Methylation; DNA-Binding Proteins; Epigenesis, Genetic; Female; Haploinsufficiency; Humans; Intellectual Disability; Male; Neurodevelopmental Disorders; Phenotype; RNA-Binding Proteins; Young Adult

SVEP1 is a human coronary artery disease locus that promotes atherosclerosis. - Jung, In-Hyuk; Elenbaas, Jared S; Alisio, Arturo; Santana, Katherine; Young, Erica P; Kang, Chul Joo; Kachroo, Puja; Lavine, Kory J; Razani, Babak; Mecham, Robert P; Stitziel, Nathan O (Sci Transl Med, 2021)
A low-frequency variant of sushi, von Willebrand factor type A, EGF, and pentraxin domain-containing protein 1 (SVEP1), an extracellular matrix protein, is associated with risk of coronary disease in humans independent of plasma lipids. Despite a robust statistical association, if and how SVEP1 might contribute to atherosclerosis remained unclear. Here, using Mendelian randomization and complementary mouse models, we provide evidence that SVEP1 promotes atherosclerosis in humans and mice and is expressed by vascular smooth muscle cells (VSMCs) within the atherosclerotic plaque. VSMCs also interact with SVEP1, causing proliferation and dysregulation of key differentiation pathways, including integrin and Notch signaling. Fibroblast growth factor receptor transcription increases in VSMCs interacting with SVEP1 and is further increased by the coronary disease-associated variant p.D2702G. These effects ultimately drive inflammation and promote atherosclerosis. Together, our results suggest that VSMC-derived SVEP1 is a proatherogenic factor and support the concept that pharmacological inhibition of SVEP1 should protect against atherosclerosis in humans.

TMEM218 dysfunction causes ciliopathies, including Joubert and Meckel syndromes. - Van De Weghe, Julie C; Giordano, Jessica L; Mathijssen, Inge B; Mojarrad, Majid; Lugtenberg, Dorien; Miller, Caitlin V; Dempsey, Jennifer C; Mohajeri, Mahsa Sadat Asl; van Leeuwen, Elizabeth; Pajkrt, Eva; Klaver, Caroline C W; Houlden, Henry; et al. (HGG Adv, 2021)
The Joubert-Meckel syndrome spectrum is a continuum of recessive ciliopathy conditions caused by primary cilium dysfunction. The primary cilium is a microtubule-based, antenna-like organelle that projects from the surface of most human cell types, allowing them to respond to extracellular signals. The cilium is partitioned from the cell body by the transition zone, a known hotspot for ciliopathy-related proteins. Despite years of Joubert syndrome (JBTS) gene discovery, the genetic cause cannot be identified in up to 30% of individuals with JBTS, depending on the cohort, sequencing method, and criteria for pathogenic variants. Using exome and targeted sequencing of 655 families with JBTS, we identified three individuals from two families harboring biallelic, rare, predicted-deleterious missense variants. Via MatchMaker Exchange, we identified biallelic variants in four additional families with ciliopathy phenotypes. Of note, four of the six families carry missense variants affecting the same highly conserved amino acid position 115. Clinical features included the molar tooth sign (N = 2), occipital encephalocele (N = 5, all fetuses), retinal dystrophy (N = 4, all living individuals), polycystic kidneys (N = 2), and polydactyly (N = 2), without liver involvement. Combined with existing functional data linking TMEM218 to ciliary transition zone function, our human genetic data make a strong case for TMEM218 dysfunction as a cause of ciliopathy phenotypes including JBTS with retinal dystrophy and Meckel syndrome. Identifying all genetic causes of the Joubert-Meckel spectrum enables diagnostic testing, prognostic and recurrence risk counseling, and medical monitoring, as well as work to delineate the underlying biological mechanisms and identify targets for future therapies.

Towards population-scale long-read sequencing. - De Coster, Wouter; Weissensteiner, Matthias H; Sedlazeck, Fritz J (Nat Rev Genet, 2021)
Long-read sequencing technologies have now reached a level of accuracy and yield that allows their application to variant detection at a scale of tens to thousands of samples. Concomitant with the development of new computational tools, the first population-scale studies involving long-read sequencing have emerged over the past 2 years and, given the continuous advancement of the field, many more are likely to follow. In this Review, we survey recent developments in population-scale long-read sequencing, highlight potential challenges of a scaled-up approach and provide guidance regarding experimental design. We provide an overview of current long-read sequencing platforms, variant calling methodologies and approaches for de novo assemblies and reference-based mapping approaches. Furthermore, we summarize strategies for variant validation, genotyping and predicting functional impact and emphasize challenges remaining in achieving long-read sequencing at a population scale.

Transethnic Transferability of a Genome-Wide Polygenic Score for Coronary Artery Disease. - Fahed, Akl C; Aragam, Krishna G; Hindy, George; Chen, Yii-Der Ida; Chaudhary, Kumardeep; Dobbyn, Amanda; Krumholz, Harlan M; Sheu, Wayne H H; Rich, Stephen S; Rotter, Jerome I; Chowdhury, Rajiv; Cho, Judy; et al. (Circ Genom Precis Med, 2021)

Two novel bi-allelic KDELR2 missense variants cause osteogenesis imperfecta with neurodevelopmental features. - Efthymiou, Stephanie; Herman, Isabella; Rahman, Fatima; Anwar, Najwa; Maroofian, Reza; Yip, Janice; Mitani, Tadahiro; Calame, Daniel G; Hunter, Jill V; Sutton, V Reid; Yilmaz Gulec, Elif; Duan, Ruizhi; et al. (Am J Med Genet A, 2021)

Typical achondroplasia secondary to a unique insertional variant of FGFR3 with in vitro demonstration of its effect on FGFR3 function. - Meyer, April N; Modaff, Peggy; Wang, Clark G; Wohler, Elizabeth; Sobreira, Nara L; Donoghue, Daniel J; Pauli, Richard M (Am J Med Genet A, 2021)
We describe an individual in whom clinical and radiographic features are typical for achondroplasia, but in whom the common variants of FGFR3 that result in achondroplasia are absent. Whole exome sequencing demonstrated a novel, de novo 6 base pair tandem duplication in FGFR3 that results in the insertion of Ser-Phe after position Leu324. in vitro studies showed that this variant results in aberrant dimerization, excessive spontaneous phosphorylation of FGFR3 dimers and excessive, ligand-independent tyrosine kinase activity. Together, these data suggest that this variant leads to constitutive disulfide bond-mediated dimerization, and that this, surprisingly, occurs to an extent similar to the neonatal lethal thanatophoric dysplasia type I Ser249Cys variant.

Variants in GNAI1 cause a syndrome associated with variable features including developmental delay, seizures, and hypotonia. - Muir, Alison M; Gardner, Jennifer F; van Jaarsveld, Richard H; de Lange, Iris M; van der Smagt, Jasper J; Wilson, Golder N; Dubbs, Holly; Goldberg, Ethan M; Zitano, Lia; Bupp, Caleb; Martinez, Jose; Srour, Myriam; et al. (Genet Med, 2021)
PURPOSE: Neurodevelopmental disorders (NDDs) encompass a spectrum of genetically heterogeneous disorders with features that commonly include developmental delay, intellectual disability, and autism spectrum disorders. We sought to delineate the molecular and phenotypic spectrum of a novel neurodevelopmental disorder caused by variants in the GNAI1 gene. METHODS: Through large cohort trio-based exome sequencing and international data-sharing, we identified 24 unrelated individuals with NDD phenotypes and a variant in GNAI1, which encodes the inhibitory Gαi1 subunit of heterotrimeric G-proteins. We collected detailed genotype and phenotype information for each affected individual. RESULTS: We identified 16 unique variants in GNAI1 in 24 affected individuals; 23 occurred de novo and 1 was inherited from a mosaic parent. Most affected individuals have a severe neurodevelopmental disorder. Core features include global developmental delay, intellectual disability, hypotonia, and epilepsy. CONCLUSION: This collaboration establishes GNAI1 variants as a cause of NDDs. GNAI1-related NDD is most often characterized by severe to profound delays, hypotonia, epilepsy that ranges from self-limiting to intractable, behavior problems, and variable mild dysmorphic features.
Keywords: Child; Developmental Disabilities; Humans; Intellectual Disability; Muscle Hypotonia; Neurodevelopmental Disorders; Seizures; Whole Exome Sequencing

Viral infections in humans and mice with genetic deficiencies of the type I IFN response pathway. - Meyts, Isabelle; Casanova, Jean-Laurent (Eur J Immunol, 2021)
Type I IFNs are so-named because they interfere with viral infection in vertebrate cells. The study of cellular responses to type I IFNs led to the discovery of the JAK-STAT signaling pathway, which also governs the response to other cytokine families. We review here the outcome of viral infections in mice and humans with engineered and inborn deficiencies, respectively, of (i) IFNAR1 or IFNAR2, selectively disrupting responses to type I IFNs, (ii) STAT1, STAT2, and IRF9, also impairing cellular responses to type II (for STAT1) and/or III (for STAT1, STAT2, IRF9) IFNs, and (iii) JAK1 and TYK2, also impairing cellular responses to cytokines other than IFNs. A picture is emerging of greater redundancy of human type I IFNs for protective immunity to viruses in natural conditions than was initially anticipated. Mouse type I IFNs are essential for protection against a broad range of viruses in experimental conditions. These findings suggest that various type I IFN-independent mechanisms of human cell-intrinsic immunity to viruses have yet to be discovered.

Whole-genome sequencing of African Americans implicates differential genetic architecture in inflammatory bowel disease. - Somineni, Hari K; Nagpal, Sini; Venkateswaran, Suresh; Cutler, David J; Okou, David T; Haritunians, Talin; Simpson, Claire L; Begum, Ferdouse; Datta, Lisa W; Quiros, Antonio J; Seminerio, Jenifer; Mengesha, Emebet; et al. (Am J Hum Genet, 2021)
Whether or not populations diverge with respect to the genetic contribution to risk of specific complex diseases is relevant to understanding the evolution of susceptibility and origins of health disparities. Here, we describe a large-scale whole-genome sequencing study of inflammatory bowel disease encompassing 1,774 affected individuals and 1,644 healthy control Americans with African ancestry (African Americans). Although no new loci for inflammatory bowel disease are discovered at genome-wide significance levels, we identify numerous instances of differential effect sizes in combination with divergent allele frequencies. For example, the major effect at PTGER4 fine maps to a single credible interval of 22 SNPs corresponding to one of four independent associations at the locus in European ancestry individuals but with an elevated odds ratio for Crohn disease in African Americans. A rare variant aggregate analysis implicates Ca-binding neuro-immunomodulator CALB2 in ulcerative colitis. Highly significant overall overlap of common variant risk for inflammatory bowel disease susceptibility between individuals with African and European ancestries was observed, with 41 of 241 previously known lead variants replicated and overall correlations in effect sizes of 0.68 for combined inflammatory bowel disease. Nevertheless, subtle differences influence the performance of polygenic risk scores, and we show that ancestry-appropriate weights significantly improve polygenic prediction in the highest percentiles of risk. The median amount of variance explained per locus remains the same in African and European cohorts, providing evidence for compensation of effect sizes as allele frequencies diverge, as expected under a highly polygenic model of disease.
Keywords: African Americans; Aged; Aged, 80 and over; Calbindin 2; Colitis, Ulcerative; Crohn Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inflammatory Bowel Diseases; Male; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Receptors, Prostaglandin E, EP4 Subtype; Whole Genome Sequencing

8q24 genetic variation and comprehensive haplotypes altering familial risk of prostate cancer. - Dupont, William D; Breyer, Joan P; Plummer, W Dale; Chang, Sam S; Cookson, Michael S; Smith, Joseph A; Blue, Elizabeth E; Bamshad, Michael J; Smith, Jeffrey R (Nat Commun, 2020)
The 8q24 genomic locus is tied to the origin of numerous cancers. We investigate its contribution to hereditary prostate cancer (HPC) in independent study populations of the Nashville Familial Prostate Cancer Study and International Consortium for Prostate Cancer Genetics (combined: 2,836 HPC cases, 2,206 controls of European ancestry). Here we report 433 variants concordantly associated with HPC in both study populations, accounting for 9% of heritability and modifying age of diagnosis as well as aggressiveness; 183 reach genome-wide significance. The variants comprehensively distinguish independent risk-altering haplotypes overlapping the 648 kb locus (three protective, and four risk (peak odds ratios: 1.5, 4, 5, and 22)). Sequence of the near-Mendelian haplotype reveals eleven causal mutation candidates. We introduce a linkage disequilibrium-based algorithm discerning eight independent sentinel variants, carrying considerable risk prediction ability (AUC = 0.625) for a single locus. These findings elucidate 8q24 locus structure and correlates for clinical prediction of prostate cancer risk.
Keywords: Aged; Case-Control Studies; Chromosomes, Human, Pair 8; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Haplotypes; Heterozygote; Humans; Linkage Disequilibrium; Male; Middle Aged; Mutation; Prostatic Neoplasms; Protective Factors; Risk Factors

Adult-onset very-long-chain acyl-CoA dehydrogenase deficiency (VLCADD). - Fatehi, F; Okhovat, A A; Nilipour, Y; Mroczek, M; Straub, V; Töpf, A; Palibrk, A; Peric, S; Rakocevic Stojanovic, V; Najmabadi, H; Nafissi, S (Eur J Neurol, 2020)
BACKGROUND AND PURPOSE: Very-long-chain acyl-CoA dehydrogenase deficiency (VLCADD) is a hereditary disorder of mitochondrial long-chain fatty acid oxidation that has variable presentations, including exercise intolerance, cardiomyopathy and liver disease. The aim of this study was to describe the clinical and genetic manifestations of six patients with adult-onset VLCADD. METHODS: In this study, the clinical, pathological and genetic findings of six adult patients (four from Iran and two from Serbia) with VLCADD and their response to treatment are described. RESULTS: The median (range) age of patients at first visit was 31 (27-38) years, and the median (range) age of onset was 26.5 (19-33) years. Parental consanguinity was present for four patients. Four patients had a history of rhabdomyolysis, and the recorded CK level ranged between 67 and 90 000 IU/l. Three patients had a history of exertional myalgia, and one patient had a non-fluctuating weakness. Through next-generation sequencing analysis, we identified six cases with variants in the ACADVL gene and a confirmed diagnosis of VLCADD. Of the total six variants identified, five were missense, and one was a novel frameshift mutation identified in two unrelated individuals. Two variants were novel, and three were previously reported. We treated the patients with a combination of L-carnitine, Coenzyme Q10 and riboflavin. Three patients responded favorably to the treatment. CONCLUSION: Adult-onset VLCADD is a rare entity with various presentations. Patients may respond favorably to a cocktail of L-carnitine, Coenzyme Q10, and riboflavin.

Analysis of cardiac magnetic resonance imaging in 36,000 individuals yields genetic insights into dilated cardiomyopathy. - Pirruccello, James P; Bick, Alexander; Wang, Minxian; Chaffin, Mark; Friedman, Samuel; Yao, Jie; Guo, Xiuqing; Venkatesh, Bharath Ambale; Taylor, Kent D; Post, Wendy S; Rich, Stephen; Lima, Joao A C; et al. (Nat Commun, 2020)
Dilated cardiomyopathy (DCM) is an important cause of heart failure and the leading indication for heart transplantation. Many rare genetic variants have been associated with DCM, but common variant studies of the disease have yielded few associated loci. As structural changes in the heart are a defining feature of DCM, we report a genome-wide association study of cardiac magnetic resonance imaging (MRI)-derived left ventricular measurements in 36,041 UK Biobank participants, with replication in 2184 participants from the Multi-Ethnic Study of Atherosclerosis. We identify 45 previously unreported loci associated with cardiac structure and function, many near well-established genes for Mendelian cardiomyopathies. A polygenic score of MRI-derived left ventricular end systolic volume strongly associates with incident DCM in the general population. Even among carriers of TTN truncating mutations, this polygenic score influences the size and function of the human heart. These results further implicate common genetic polymorphisms in the pathogenesis of DCM.
Keywords: Cardiomyopathy, Dilated; Genome-Wide Association Study; Heart; Humans; Magnetic Resonance Imaging; Myocardium; Polymorphism, Single Nucleotide

ASC-1 Is a Cell Cycle Regulator Associated with Severe and Mild Forms of Myopathy. - Villar-Quiles, Rocío N; Catervi, Fabio; Cabet, Eva; Juntas-Morales, Raul; Genetti, Casie A; Gidaro, Teresa; Koparir, Asuman; Yuksel, Adnan; Coppens, Sandra; Deconinck, Nicolas; Pierce-Hoffman, Emma; Lornage, Xavière; et al. (Ann Neurol, 2020)
OBJECTIVE: Recently, the ASC-1 complex has been identified as a mechanistic link between amyotrophic lateral sclerosis and spinal muscular atrophy (SMA), and 3 mutations of the ASC-1 gene TRIP4 have been associated with SMA or congenital myopathy. Our goal was to define ASC-1 neuromuscular function and the phenotypical spectrum associated with TRIP4 mutations. METHODS: Clinical, molecular, histological, and magnetic resonance imaging studies were made in 5 families with 7 novel TRIP4 mutations. Fluorescence activated cell sorting and Western blot were performed in patient-derived fibroblasts and muscles and in Trip4 knocked-down C2C12 cells. RESULTS: All mutations caused ASC-1 protein depletion. The clinical phenotype was purely myopathic, ranging from lethal neonatal to mild ambulatory adult patients. It included early onset axial and proximal weakness, scoliosis, rigid spine, dysmorphic facies, cutaneous involvement, respiratory failure, and in the older cases, dilated cardiomyopathy. Muscle biopsies showed multiminicores, nemaline rods, cytoplasmic bodies, caps, central nuclei, rimmed fibers, and/or mild endomysial fibrosis. ASC-1 depletion in C2C12 and in patient-derived fibroblasts and muscles caused accelerated proliferation, altered expression of cell cycle proteins, and/or shortening of the G0/G1 cell cycle phase leading to cell size reduction. INTERPRETATION: Our results expand the phenotypical and molecular spectrum of TRIP4-associated disease to include mild adult forms with or without cardiomyopathy, associate ASC-1 depletion with isolated primary muscle involvement, and establish TRIP4 as a causative gene for several congenital muscle diseases, including nemaline, core, centronuclear, and cytoplasmic-body myopathies. They also identify ASC-1 as a novel cell cycle regulator with a key role in cell proliferation, and underline transcriptional coregulation defects as a novel pathophysiological mechanism. ANN NEUROL 2020;87:217-232.
Keywords: Adult; Amino Acid Transport System y+; Cell Cycle; Cells, Cultured; Child; Child, Preschool; Female; Fibroblasts; Humans; Infant; Male; Middle Aged; Muscle Proteins; Muscle, Skeletal; Muscular Diseases; Mutation; Pedigree; Phenotype; Transcription Factors

Association of Rare Pathogenic DNA Variants for Familial Hypercholesterolemia, Hereditary Breast and Ovarian Cancer Syndrome, and Lynch Syndrome With Disease Risk in Adults According to Family History. - Patel, Aniruddh P; Wang, Minxian; Fahed, Akl C; Mason-Suares, Heather; Brockman, Deanna; Pelletier, Renee; Amr, Sami; Machini, Kalotina; Hawley, Megan; Witkowski, Leora; Koch, Christopher; Philippakis, Anthony; et al. (JAMA Netw Open, 2020)
Importance: Pathogenic DNA variants associated with familial hypercholesterolemia, hereditary breast and ovarian cancer syndrome, and Lynch syndrome are widely recognized as clinically important and actionable when identified, leading some clinicians to recommend population-wide genomic screening. Objectives: To assess the prevalence and clinical importance of pathogenic or likely pathogenic variants associated with each of 3 genomic conditions (familial hypercholesterolemia, hereditary breast and ovarian cancer syndrome, and Lynch syndrome) within the context of contemporary clinical care. Design, Setting, and Participants: This cohort study used gene-sequencing data from 49 738 participants in the UK Biobank who were recruited from 22 sites across the UK between March 21, 2006, and October 1, 2010. Inpatient hospital data date back to 1977; cancer registry data, to 1957; and death registry data, to 2006. Statistical analysis was performed from July 22, 2019, to November 15, 2019. Exposures: Pathogenic or likely pathogenic DNA variants classified by a clinical laboratory geneticist. Main Outcomes and Measures: Composite end point specific to each genomic condition based on atherosclerotic cardiovascular disease events for familial hypercholesterolemia, breast or ovarian cancer for hereditary breast and ovarian cancer syndrome, and colorectal or uterine cancer for Lynch syndrome. Results: Among 49 738 participants (mean [SD] age, 57 [8] years; 27 144 female [55%]), 441 (0.9%) harbored a pathogenic or likely pathogenic variant associated with any of 3 genomic conditions, including 131 (0.3%) for familial hypercholesterolemia, 235 (0.5%) for hereditary breast and ovarian cancer syndrome, and 76 (0.2%) for Lynch syndrome. Presence of these variants was associated with increased risk of disease: for familial hypercholesterolemia, 28 of 131 carriers (21.4%) vs 4663 of 49 607 noncarriers (9.4%) developed atherosclerotic cardiovascular disease; for hereditary breast and ovarian cancer syndrome, 32 of 116 female carriers (27.6%) vs 2080 of 27 028 female noncarriers (7.7%) developed associated cancers; and for Lynch syndrome, 17 of 76 carriers (22.4%) vs 929 of 49 662 noncarriers (1.9%) developed colorectal or uterine cancer. The predicted probability of disease at age 75 years despite contemporary clinical care was 45.3% for carriers of familial hypercholesterolemia, 41.1% for hereditary breast and ovarian cancer syndrome, and 38.3% for Lynch syndrome. Across the 3 conditions, 39.7% (175 of 441) of the carriers reported a family history of disease vs 23.2% (34 517 of 148 772) of noncarriers. Conclusions and Relevance: The findings suggest that approximately 1% of the middle-aged adult population in the UK Biobank harbored a pathogenic variant associated with any of 3 genomic conditions. These variants were associated with an increased risk of disease despite contemporary clinical care and were not reliably detected by family history.
Keywords: Aged; Cohort Studies; Colorectal Neoplasms, Hereditary Nonpolyposis; Female; Genetic Predisposition to Disease; Hereditary Breast and Ovarian Cancer Syndrome; Heterozygote; Humans; Hyperlipoproteinemia Type II; Male; Middle Aged; Pedigree; Proportional Hazards Models; United Kingdom; Whole Exome Sequencing

Autoantibodies against type I IFNs in patients with life-threatening COVID-19. - Bastard, Paul; Rosen, Lindsey B; Zhang, Qian; Michailidis, Eleftherios; Hoffmann, Hans-Heinrich; Zhang, Yu; Dorgham, Karim; Philippot, Quentin; Rosain, Jérémie; Béziat, Vivien; Manry, Jeremy; Shaw, Elana; et al. (Science, 2020)
Interindividual clinical variability in the course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is vast. We report that at least 101 of 987 patients with life-threatening coronavirus disease 2019 (COVID-19) pneumonia had neutralizing immunoglobulin G (IgG) autoantibodies (auto-Abs) against interferon-ω (IFN-ω) (13 patients), against the 13 types of IFN-α (36), or against both (52) at the onset of critical disease; a few also had auto-Abs against the other three type I IFNs. The auto-Abs neutralize the ability of the corresponding type I IFNs to block SARS-CoV-2 infection in vitro. These auto-Abs were not found in 663 individuals with asymptomatic or mild SARS-CoV-2 infection and were present in only 4 of 1227 healthy individuals. Patients with auto-Abs were aged 25 to 87 years and 95 of the 101 were men. A B cell autoimmune phenocopy of inborn errors of type I IFN immunity accounts for life-threatening COVID-19 pneumonia in at least 2.6% of women and 12.5% of men.
Keywords: Adult; Aged; Aged, 80 and over; Antibodies, Neutralizing; Asymptomatic Infections; Autoantibodies; Betacoronavirus; Case-Control Studies; Coronavirus Infections; COVID-19; Critical Illness; Female; Humans; Immunoglobulin G; Interferon alpha-2; Interferon Type I; Male; Middle Aged; Pandemics; Pneumonia, Viral; SARS-CoV-2

Beyond the tubule: pathological variants of , encoding the megalin receptor, result in glomerular loss and early progressive chronic kidney disease. - Charlton, Jennifer R; Tan, Weizhen; Daouk, Ghaleb; Teot, Lisa; Rosen, Seymour; Bennett, Kevin M; Cwiek, Aleksandra; Nam, Sejin; Emma, Francesco; Jouret, François; Oliveira, João Paulo; Tranebjærg, Lisbeth; et al. (Am J Physiol Renal Physiol, 2020)
Pathogenic variants in the gene, encoding the multiligand receptor megalin, cause a rare autosomal recessive syndrome: Donnai-Barrow/Facio-Oculo-Acoustico-Renal (DB/FOAR) syndrome. Because of the rarity of the syndrome, the long-term consequences of the tubulopathy on human renal health have been difficult to ascertain, and the human clinical condition has hitherto been characterized as a benign tubular condition with asymptomatic low-molecular-weight proteinuria. We investigated renal function and morphology in a murine model of DB/FOAR syndrome and in patients with DB/FOAR. We analyzed glomerular filtration rate in mice by FITC-inulin clearance and clinically characterized six families, including nine patients with DB/FOAR and nine family members. Urine samples from patients were analyzed by Western blot analysis and biopsy materials were analyzed by histology. In the mouse model, we used histological methods to assess nephrogenesis and postnatal renal structure and contrast-enhanced magnetic resonance imaging to assess glomerular number. In megalin-deficient mice, we found a lower glomerular filtration rate and an increase in the abundance of injury markers, such as kidney injury molecule-1 and -acetyl-β-d-glucosaminidase. Renal injury was validated in patients, who presented with increased urinary kidney injury molecule-1, classical markers of chronic kidney disease, and glomerular proteinuria early in life. Megalin-deficient mice had normal nephrogenesis, but they had 19% fewer nephrons in early adulthood and an increased fraction of nephrons with disconnected glomerulotubular junction. In conclusion, megalin dysfunction, as present in DB/FOAR syndrome, confers an increased risk of progression into chronic kidney disease.
Keywords: Adolescent; Adult; Animals; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Kidney Glomerulus; Low Density Lipoprotein Receptor-Related Protein-2; Male; Mice; Mice, Knockout; Middle Aged; Renal Insufficiency, Chronic; Young Adult

Bi-allelic ADARB1 Variants Associated with Microcephaly, Intellectual Disability, and Seizures. - Tan, Tiong Yang; Sedmík, Jiří; Fitzgerald, Mark P; Halevy, Rivka Sukenik; Keegan, Liam P; Helbig, Ingo; Basel-Salmon, Lina; Cohen, Lior; Straussberg, Rachel; Chung, Wendy K; Helal, Mayada; Maroofian, Reza; et al. (Am J Hum Genet, 2020)
The RNA editing enzyme ADAR2 is essential for the recoding of brain transcripts. Impaired ADAR2 editing leads to early-onset epilepsy and premature death in a mouse model. Here, we report bi-allelic variants in ADARB1, the gene encoding ADAR2, in four unrelated individuals with microcephaly, intellectual disability, and epilepsy. In one individual, a homozygous variant in one of the double-stranded RNA-binding domains (dsRBDs) was identified. In the others, variants were situated in or around the deaminase domain. To evaluate the effects of these variants on ADAR2 enzymatic activity, we performed in vitro assays with recombinant proteins in HEK293T cells and ex vivo assays with fibroblasts derived from one of the individuals. We demonstrate that these ADAR2 variants lead to reduced editing activity on a known ADAR2 substrate. We also demonstrate that one variant leads to changes in splicing of ADARB1 transcript isoforms. These findings reinforce the importance of RNA editing in brain development and introduce ADARB1 as a genetic etiology in individuals with intellectual disability, microcephaly, and epilepsy.
Keywords: Adenosine Deaminase; Alleles; Alternative Splicing; Child; Child, Preschool; Genetic Predisposition to Disease; Genetic Variation; HEK293 Cells; Humans; Intellectual Disability; Male; Microcephaly; RNA Splicing; RNA-Binding Proteins; Seizures

Bi-allelic GAD1 variants cause a neonatal onset syndromic developmental and epileptic encephalopathy. - Chatron, Nicolas; Becker, Felicitas; Morsy, Heba; Schmidts, Miriam; Hardies, Katia; Tuysuz, Beyhan; Roselli, Sandra; Najafi, Maryam; Alkaya, Dilek Uludag; Ashrafzadeh, Farah; Nabil, Amira; Omar, Tarek; et al. (Brain, 2020)
Developmental and epileptic encephalopathies are a heterogeneous group of early-onset epilepsy syndromes dramatically impairing neurodevelopment. Modern genomic technologies have revealed a number of monogenic origins and opened the door to therapeutic hopes. Here we describe a new syndromic developmental and epileptic encephalopathy caused by bi-allelic loss-of-function variants in GAD1, as presented by 11 patients from six independent consanguineous families. Seizure onset occurred in the first 2 months of life in all patients. All 10 patients, from whom early disease history was available, presented with seizure onset in the first month of life, mainly consisting of epileptic spasms or myoclonic seizures. Early EEG showed suppression-burst or pattern of burst attenuation or hypsarrhythmia if only recorded in the post-neonatal period. Eight patients had joint contractures and/or pes equinovarus. Seven patients presented a cleft palate and two also had an omphalocele, reproducing the phenotype of the knockout Gad1-/- mouse model. Four patients died before 4 years of age. GAD1 encodes the glutamate decarboxylase enzyme GAD67, a critical actor of the γ-aminobutyric acid (GABA) metabolism as it catalyses the decarboxylation of glutamic acid to form GABA. Our findings evoke a novel syndrome related to GAD67 deficiency, characterized by the unique association of developmental and epileptic encephalopathies, cleft palate, joint contractures and/or omphalocele.
Keywords: Abnormalities, Multiple; Epileptic Syndromes; Female; Glutamate Decarboxylase; Humans; Infant, Newborn; Male; Mutation; Pedigree

Biallelic GRM7 variants cause epilepsy, microcephaly, and cerebral atrophy. - Marafi, Dana; Mitani, Tadahiro; Isikay, Sedat; Hertecant, Jozef; Almannai, Mohammed; Manickam, Kandamurugu; Abou Jamra, Rami; El-Hattab, Ayman W; Rajah, Jaishen; Fatih, Jawid M; Du, Haowei; Karaca, Ender; et al. (Ann Clin Transl Neurol, 2020)
OBJECTIVE: Defects in ion channels and neurotransmitter receptors are implicated in developmental and epileptic encephalopathy (DEE). Metabotropic glutamate receptor 7 (mGluR7), encoded by GRM7, is a presynaptic G-protein-coupled glutamate receptor critical for synaptic transmission. We previously proposed GRM7 as a candidate disease gene in two families with neurodevelopmental disorders (NDDs). One additional family has been published since. Here, we describe three additional families with GRM7 biallelic variants and deeply characterize the associated clinical neurological and electrophysiological phenotype and molecular data in 11 affected individuals from six unrelated families. METHODS: Exome sequencing and family-based rare variant analyses on a cohort of 220 consanguineous families with NDDs revealed three families with GRM7 biallelic variants; three additional families were identified through literature search and collaboration with a clinical molecular laboratory. RESULTS: We compared the observed clinical features and variants of 11 affected individuals from the six unrelated families. Identified novel deleterious variants included two homozygous missense variants (c.2671G>A:p.Glu891Lys and c.1973G>A:p.Arg685Gln) and one homozygous stop-gain variant (c.1975C>T:p.Arg659Ter). Developmental delay, neonatal- or infantile-onset epilepsy, and microcephaly were universal. Three individuals had hypothalamic-pituitary-axis dysfunction without pituitary structural abnormality. Neuroimaging showed cerebral atrophy and hypomyelination in a majority of cases. Two siblings demonstrated progressive loss of myelination by 2 years in both and an acquired microcephaly pattern in one. Five individuals died in early or late childhood. CONCLUSION: Detailed clinical characterization of 11 individuals from six unrelated families demonstrates that rare biallelic GRM7 pathogenic variants can cause DEEs, microcephaly, hypomyelination, and cerebral atrophy.
Keywords: Adolescent; Alleles; Atrophy; Child; Child, Preschool; Cohort Studies; Consanguinity; Epilepsy; Female; Humans; Infant; Male; Microcephaly; Neurodevelopmental Disorders; Pedigree; Phenotype; Receptors, Metabotropic Glutamate; Whole Exome Sequencing

Biallelic in-frame deletion in TRAPPC4 in a family with developmental delay and cerebellar atrophy. - Saad, Ahmed K; Marafi, Dana; Mitani, Tadahiro; Jolly, Angad; Du, Haowei; Elbendary, Hasnaa M; Jhangiani, Shalini N; Akdemir, Zeynep C; Gibbs, Richard A; Hunter, Jill V; Carvalho, Claudia M B C; Pehlivan, Davut; et al. (Brain, 2020)
Keywords: Atrophy; Cerebellar Diseases; Humans; Intellectual Disability; Sequence Deletion

Biallelic loss of function variants in SYT2 cause a treatable congenital onset presynaptic myasthenic syndrome. - Donkervoort, Sandra; Mohassel, Payam; Laugwitz, Lucia; Zaki, MAH S; Kamsteeg, Erik-Jan; Maroofian, Reza; Chao, Katherine R; Verschuuren-Bemelmans, Corien C; Horber, Veronka; Fock, Annemarie J M; McCarty, Riley M; Jain, Minal S; et al. (Am J Med Genet A, 2020)
Synaptotagmins are integral synaptic vesicle membrane proteins that function as calcium sensors and regulate neurotransmitter release at the presynaptic nerve terminal. Synaptotagmin-2 (SYT2), is the major isoform expressed at the neuromuscular junction. Recently, dominant missense variants in SYT2 have been reported as a rare cause of distal motor neuropathy and myasthenic syndrome, manifesting with stable or slowly progressive distal weakness of variable severity along with presynaptic NMJ impairment. These variants are thought to have a dominant-negative effect on synaptic vesicle exocytosis, although the precise pathomechanism remains to be elucidated. Here we report seven patients of five families, with biallelic loss of function variants in SYT2, clinically manifesting with a remarkably consistent phenotype of severe congenital onset hypotonia and weakness, with variable degrees of respiratory involvement. Electrodiagnostic findings were consistent with a presynaptic congenital myasthenic syndrome (CMS) in some. Treatment with an acetylcholinesterase inhibitor pursued in three patients showed clinical improvement with increased strength and function. This series further establishes SYT2 as a CMS-disease gene and expands its clinical and genetic spectrum to include recessive loss-of-function variants, manifesting as a severe congenital onset presynaptic CMS with potential treatment implications.
Keywords: Adolescent; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Male; Muscle Hypotonia; Muscle Weakness; Mutation, Missense; Myasthenic Syndromes, Congenital; Pedigree; Phenotype; Synaptic Transmission; Synaptotagmin II

Biallelic mutations in LAMA5 disrupts a skeletal noncanonical focal adhesion pathway and produces a distinct bent bone dysplasia. - Barad, Maya; Csukasi, Fabiana; Bosakova, Michaela; Martin, Jorge H; Zhang, Wenjuan; Paige Taylor, S; Lachman, Ralph S; Zieba, Jennifer; Bamshad, Michael; Nickerson, Deborah; Chong, Jessica X; Cohn, Daniel H; et al. (EBioMedicine, 2020)
BACKGROUND: Beyond its structural role in the skeleton, the extracellular matrix (ECM), particularly basement membrane proteins, facilitates communication with intracellular signaling pathways and cell to cell interactions to control differentiation, proliferation, migration and survival. Alterations in extracellular proteins cause a number of skeletal disorders, yet the consequences of an abnormal ECM on cellular communication remains less well understood METHODS: Clinical and radiographic examinations defined the phenotype in this unappreciated bent bone skeletal disorder. Exome analysis identified the genetic alteration, confirmed by Sanger sequencing. Quantitative PCR, western blot analyses, immunohistochemistry, luciferase assay for WNT signaling were employed to determine RNA, proteins levels and localization, and dissect out the underlying cell signaling abnormalities.  Migration and wound healing assays examined cell migration properties. FINDINGS: This bent bone dysplasia resulted from biallelic mutations in LAMA5, the gene encoding the alpha-5 laminin basement membrane protein. This finding uncovered a mechanism of disease driven by ECM-cell interactions between alpha-5-containing laminins, and integrin-mediated focal adhesion signaling, particularly in cartilage. Loss of LAMA5 altered β1 integrin signaling through the non-canonical kinase PYK2 and the skeletal enriched SRC kinase, FYN. Loss of LAMA5 negatively impacted the actin cytoskeleton, vinculin localization, and WNT signaling. INTERPRETATION: This newly described mechanism revealed a LAMA5-β1 Integrin-PYK2-FYN focal adhesion complex that regulates skeletogenesis, impacted WNT signaling and, when dysregulated, produced a distinct skeletal disorder. FUNDING: Supported by NIH awards R01 AR066124, R01 DE019567, R01 HD070394, and U54HG006493, and Czech Republic grants INTER-ACTION LTAUSA19030, V18-08-00567 and GA19-20123S.

Bi-allelic Variations of SMO in Humans Cause a Broad Spectrum of Developmental Anomalies Due to Abnormal Hedgehog Signaling. - Le, Thuy-Linh; Sribudiani, Yunia; Dong, Xiaomin; Huber, Celine; Kois, Chelsea; Baujat, Geneviève; Gordon, Christopher T; Mayne, Valerie; Galmiche, Louise; Serre, Valérie; Goudin, Nicolas; Zarhrate, Mohammed; et al. (Am J Hum Genet, 2020)
The evolutionarily conserved hedgehog (Hh) pathway is essential for organogenesis and plays critical roles in postnatal tissue maintenance and renewal. A unique feature of the vertebrate Hh pathway is that signal transduction requires the primary cilium (PC) where major pathway components are dynamically enriched. These factors include smoothened (SMO) and patched, which constitute the core reception system for sonic hedgehog (SHH) as well as GLI transcription factors, the key mediators of the pathway. Here, we report bi-allelic loss-of-function variations in SMO in seven individuals from five independent families; these variations cause a wide phenotypic spectrum of developmental anomalies affecting the brain (hypothalamic hamartoma and microcephaly), heart (atrioventricular septal defect), skeleton (postaxial polydactyly, narrow chest, and shortening of long bones), and enteric nervous system (aganglionosis). Cells derived from affected individuals showed normal ciliogenesis but severely altered Hh-signal transduction as a result of either altered PC trafficking or abnormal activation of the pathway downstream of SMO. In addition, Hh-independent GLI2 accumulation at the PC tip in cells from the affected individuals suggests a potential function of SMO in regulating basal ciliary trafficking of GLI2 when the pathway is off. Thus, loss of SMO function results in abnormal PC dynamics of key components of the Hh signaling pathway and leads to a large continuum of malformations in humans.
Keywords: Alleles; Base Sequence; Child; Child, Preschool; Cilia; Developmental Disabilities; Female; Hedgehog Proteins; Humans; Infant; Male; Models, Molecular; Neoplasms; Nerve Tissue Proteins; Nuclear Proteins; Pedigree; Signal Transduction; Smoothened Receptor; Zinc Finger Protein Gli2; Zinc Finger Protein Gli3

Cell type-specific genetic regulation of gene expression across human tissues. - Kim-Hellmuth, Sarah; Aguet, Francois; Oliva, Meritxell; Muñoz-Aguirre, Manuel; Kasela, Silva; Wucher, Valentin; Castel, Stephane E; Hamel, Andrew R; Viñuela, Ana; Roberts, Amy L; Mangul, Serghei; Wen, Xiaoquan; et al. (Science, 2020)
The Genotype-Tissue Expression (GTEx) project has identified expression and splicing quantitative trait loci in cis (QTLs) for the majority of genes across a wide range of human tissues. However, the functional characterization of these QTLs has been limited by the heterogeneous cellular composition of GTEx tissue samples. We mapped interactions between computational estimates of cell type abundance and genotype to identify cell type-interaction QTLs for seven cell types and show that cell type-interaction expression QTLs (eQTLs) provide finer resolution to tissue specificity than bulk tissue cis-eQTLs. Analyses of genetic associations with 87 complex traits show a contribution from cell type-interaction QTLs and enables the discovery of hundreds of previously unidentified colocalized loci that are masked in bulk tissue.
Keywords: Cells; Gene Expression Regulation; Humans; Organ Specificity; Quantitative Trait Loci; RNA, Long Noncoding; Transcriptome

Characterization of the Robinow syndrome skeletal phenotype, bone micro-architecture, and genotype-phenotype correlations with the osteosclerotic form. - Shayota, Brian J; Zhang, Chaofan; Shypailo, Roman J; Mazzeu, Juliana F; Carvalho, Claudia M B; Sutton, V Reid (Am J Med Genet A, 2020)
Robinow syndrome (RS) is a genetically heterogeneous skeletal dysplasia with recent reports suggesting an osteosclerotic form of the disease. We endeavored to investigate the full spectrum of skeletal anomalies in a genetically diverse cohort of RS patients with a focus on the bone micro-architecture. Seven individuals with molecularly confirmed RS, including four with DVL1 variants and single individuals with variants in WNT5A, ROR2, and GPC4 underwent a musculoskeletal focused physical examination, dual-energy X-ray absorptiometry (DEXA) scan, and high-resolution peripheral quantitative computed tomography (HR-pQCT). Skeletal examination revealed variability in limb shortening anomalies consistent with recent reports. DEXA scan measures revealed increased total body bone mineral density (BMD) (3/7), cranial BMD (5/7), and non-cranial BMD (1/7). Cranial osteosclerosis was only observed in DVL1-RS (4/4) and GPC4-RS (1/1) subjects and in one case was complicated by choanal atresia, bilateral conductive hearing loss, and cranial nerve III, VI, and VII palsy. HR-pQCT revealed a unique pattern of low cortical BMD, increased trabecular BMD, decreased number of trabeculations, and increased thickness of the trabeculations for the DVL1-RS subjects. The spectrum of skeletal anomalies including the micro-architecture of the bones observed in RS has considerable variability with some osteosclerosis genotype-phenotype correlations more frequent with DVL1 variants.

Clinical genomics and contextualizing genome variation in the diagnostic laboratory. - Lupski, James R; Liu, Pengfei; Stankiewicz, Pawel; Carvalho, Claudia M B; Posey, Jennifer E (Expert Rev Mol Diagn, 2020)
INTRODUCTION: The human genome contains the instructions for the development and biological homeostasis of the human organism and the genetic transmission of traits. Genome variation in human populations is the basis of evolution; individual or personal genomes vary tremendously, making each of us truly unique. AREAS COVERED: Assaying this individual variation using genomic technologies has many applications in clinical medicine, from elucidating the biology of disease to designing strategies to ameliorate perturbations from homeostasis. Detecting pathogenic rare variation in a genome may provide a molecular diagnosis that can be informative for patient management and family healthcare. EXPERT OPINION: Despite the increasing clinical use of unbiased genomic testing, including chromosome microarray analysis (CMA) with array comparative genomic hybridization (aCGH) or SNP arrays, clinical exome sequencing (cES), and whole-genome sequencing (WGS), to survey genome-wide for molecular aberrations, clinical acumen paired with an understanding of the limitations of each testing type will be needed to achieve molecular diagnoses. Potential opportunities for improving case solved rates, functionally annotating the majority of genes in the human genome, and further understanding genetic contributions to disease will empower clinical genomics and the precision medicine initiative.

CNVs cause autosomal recessive genetic diseases with or without involvement of SNV/indels. - Yuan, Bo; Wang, Lei; Liu, Pengfei; Shaw, Chad; Dai, Hongzheng; Cooper, Lance; Zhu, Wenmiao; Anderson, Stephanie A; Meng, Linyan; Wang, Xia; Wang, Yue; Xia, Fan; et al. (Genet Med, 2020)
PURPOSE: Improved resolution of molecular diagnostic technologies enabled detection of smaller sized exonic level copy-number variants (CNVs). The contribution of CNVs to autosomal recessive (AR) conditions may be better recognized using a large clinical cohort. METHODS: We retrospectively investigated the CNVs' contribution to AR conditions in cases subjected to chromosomal microarray analysis (CMA, N = ~70,000) and/or clinical exome sequencing (ES, N = ~12,000) at Baylor Genetics; most had pediatric onset neurodevelopmental disorders. RESULTS: CNVs contributed to biallelic variations in 87 cases, including 81 singletons and three affected sibling pairs. Seventy cases had CNVs affecting both alleles, and 17 had a CNV and a single-nucleotide variant (SNV)/indel in trans. In total, 94.3% of AR-CNVs affected one gene; among these 41.4% were single-exon and 35.0% were multiexon partial-gene events. Sixty-nine percent of homozygous AR-CNVs were embedded in homozygous genomic intervals. Five cases had large deletions unmasking an SNV/indel on the intact allele for a recessive condition, resulting in multiple molecular diagnoses. CONCLUSIONS: AR-CNVs are often smaller in size, transmitted through generations, and underrecognized due to limitations in clinical CNV detection methods. Our findings from a large clinical cohort emphasized integrated CNV and SNV/indel analyses for precise clinical and molecular diagnosis especially in the context of genomic disorders.
Keywords: Child; DNA Copy Number Variations; Exons; Humans; INDEL Mutation; Retrospective Studies; Whole Exome Sequencing

Collagen VI-related limb-girdle syndrome caused by frequent mutation in COL6A3 gene with conflicting reports of pathogenicity. - Stavusis, Janis; Micule, Ieva; Wright, Nathan T; Straub, Volker; Topf, Ana; Panadés-de Oliveira, Luísa; Domínguez-González, Cristina; Inashkina, Inna; Kidere, Dita; Chrestian, Nicolas; Lace, Baiba (Neuromuscul Disord, 2020)
Recently the scientific community has started to view Bethlem myopathy 1 and Ullrich congenital muscular dystrophy as two extremes of a collagen VI-related myopathy spectrum rather than two separate entities, as both are caused by mutations in one of the collagen VI genes. Here we report three individuals in two families who are homozygous for a COL6A3 mutation (c.7447A> G; p.Lys2483Glu), and compare their clinical features with seven previously published cases. Individuals carrying homozygous or compound heterozygous c.7447A> G, (p.Lys2483Glu) mutation exhibit mild phenotype without loss of ambulation, similar to the cases described previously as Collagen VI-related limb-girdle syndrome. The phenotype could arise due to an aberrant assembly of Von Willebrand factor A domains. Based on these data, we propose that c.7447A> G, (p.Lys2483Glu) is a common pathogenic mutation.

Combining Imaging and Genetics to Predict Recurrence of Anticoagulation-Associated Intracerebral Hemorrhage. - Biffi, Alessandro; Urday, Sebastian; Kubiszewski, Patryk; Gilkerson, Lee; Sekar, Padmini; Rodriguez-Torres, Axana; Bettin, Margaret; Charidimou, Andreas; Pasi, Marco; Kourkoulis, Christina; Schwab, Kristin; DiPucchio, Zora; et al. (Stroke, 2020)
BACKGROUND AND PURPOSE: For survivors of oral anticoagulation therapy (OAT)-associated intracerebral hemorrhage (OAT-ICH) who are at high risk for thromboembolism, the benefits of OAT resumption must be weighed against increased risk of recurrent hemorrhagic stroke. The ε2/ε4 alleles of the () gene, MRI-defined cortical superficial siderosis, and cerebral microbleeds are the most potent risk factors for recurrent ICH. We sought to determine whether combining MRI markers and genotype could have clinical impact by identifying ICH survivors in whom the risks of OAT resumption are highest. METHODS: Joint analysis of data from 2 longitudinal cohort studies of OAT-ICH survivors: (1) MGH-ICH study (Massachusetts General Hospital ICH) and (2) longitudinal component of the ERICH study (Ethnic/Racial Variations of Intracerebral Hemorrhage). We evaluated whether MRI markers and genotype predict ICH recurrence. We then developed and validated a combined -MRI classification scheme to predict ICH recurrence, using Classification and Regression Tree analysis. RESULTS: Cortical superficial siderosis, cerebral microbleed, and ε2/ε4 variants were independently associated with ICH recurrence after OAT-ICH (all <0.05). Combining genotype and MRI data resulted in improved prediction of ICH recurrence (Harrell C: 0.79 versus 0.55 for clinical data alone, =0.033). In the MGH (training) data set, CSS, cerebral microbleed, and ε2/ε4 stratified likelihood of ICH recurrence into high-, medium-, and low-risk categories. In the ERICH (validation) data set, yearly ICH recurrence rates for high-, medium-, and low-risk individuals were 6.6%, 2.5%, and 0.9%, respectively, with overall area under the curve of 0.91 for prediction of recurrent ICH. CONCLUSIONS: Combining MRI and genotype stratifies likelihood of ICH recurrence into high, medium, and low risk. If confirmed in prospective studies, this combined -MRI classification scheme may prove useful for selecting individuals for OAT resumption after ICH.
Keywords: Aged; Anticoagulants; Apolipoprotein E4; Cerebral Hemorrhage; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Recurrence

A common variant in PNPLA3 is associated with age at diagnosis of NAFLD in patients from a multi-ethnic biobank. - Walker, Ryan W; Belbin, Gillian M; Sorokin, Elena P; Van Vleck, Tielman; Wojcik, Genevieve L; Moscati, Arden; Gignoux, Christopher R; Cho, Judy; Abul-Husn, Noura S; Nadkarni, Girish; Kenny, Eimear E; Loos, Ruth J F (J Hepatol, 2020)
BACKGROUND & AIMS: The Ile138Met variant (rs738409) in the PNPLA3 gene has the largest effect on non-alcoholic fatty liver disease (NAFLD), increasing the risk of progression to severe forms of liver disease. It remains unknown if the variant plays a role in age of NAFLD onset. We aimed to determine if rs738409 impacts on the age of NAFLD diagnosis. METHODS: We applied a novel natural language processing (NLP) algorithm to a longitudinal electronic health records (EHR) dataset of >27,000 individuals with genetic data from a multi-ethnic biobank, defining NAFLD cases (n = 1,703) and confirming controls (n = 8,119). We conducted i) a survival analysis to determine if age at diagnosis differed by rs738409 genotype, ii) a receiver operating characteristics analysis to assess the utility of the rs738409 genotype in discriminating NAFLD cases from controls, and iii) a phenome-wide association study (PheWAS) between rs738409 and 10,095 EHR-derived disease diagnoses. RESULTS: The PNPLA3 G risk allele was associated with: i) earlier age of NAFLD diagnosis, with the strongest effect in Hispanics (hazard ratio 1.33; 95% CI 1.15-1.53; p <0.0001) among whom a NAFLD diagnosis was 15% more likely in risk allele carriers vs. non-carriers; ii) increased NAFLD risk (odds ratio 1.61; 95% CI 1.349-1.73; p <0.0001), with the strongest effect among Hispanics (odds ratio 1.43; 95% CI 1.28-1.59; p <0.0001); iii) additional liver diseases in a PheWAS (p <4.95 × 10) where the risk variant also associated with earlier age of diagnosis. CONCLUSION: Given the role of the rs738409 in NAFLD diagnosis age, our results suggest that stratifying risk within populations known to have an enhanced risk of liver disease, such as Hispanic carriers of the rs738409 variant, would be effective in earlier identification of those who would benefit most from early NAFLD prevention and treatment strategies. LAY SUMMARY: Despite clear associations between the PNPLA3 rs738409 variant and elevated risk of progression from non-alcoholic fatty liver disease (NAFLD) to more severe forms of liver disease, it remains unknown if PNPLA3 rs738409 plays a role in the age of NAFLD onset. Herein, we found that this risk variant is associated with an earlier age of NAFLD and other liver disease diagnoses; an observation most pronounced in Hispanic Americans. We conclude that PNPLA3 rs738409 could be used to better understand liver disease risk within vulnerable populations and identify patients that may benefit from early prevention strategies.

Community-based recruitment and exome sequencing indicates high diagnostic yield in adults with intellectual disability. - Sabo, Aniko; Murdock, David; Dugan, Shannon; Meng, Qingchang; Gingras, Marie-Claude; Hu, Jianhong; Muzny, Donna; Gibbs, Richard (Mol Genet Genomic Med, 2020)
BACKGROUND: Establishing a genetic diagnosis for individuals with intellectual disability (ID) benefits patients and their families as it may inform the prognosis, lead to appropriate therapy, and facilitate access to medical and supportive services. Exome sequencing has been successfully applied in a diagnostic setting, but most clinical exome referrals are pediatric patients, with many adults with ID lacking a comprehensive genetic evaluation. METHODS: Our unique recruitment strategy involved partnering with service and education providers for individuals with ID. We performed exome sequencing and analysis, and clinical variant interpretation for each recruited family. RESULTS: All five families enrolled in the study opted-in for the return of genetic results. In three out of five families exome sequencing analysis identified pathogenic or likely pathogenic variants in KANSL1, TUSC3, and MED13L genes. Families discussed the results and any potential medical follow-up in an appointment with a board certified clinical geneticist. CONCLUSION: Our study suggests high yield of exome sequencing as a diagnostic tool in adult patients with ID who have not undergone comprehensive sequencing-based genetic testing. Research studies including an option of return of results through a genetic clinic could help minimize the disparity in exome diagnostic testing between pediatric and adult patients with ID.
Keywords: Adult; Female; Genetic Testing; Humans; Independent Living; Intellectual Disability; Male; Mediator Complex; Membrane Proteins; Nuclear Proteins; Patient Selection; Sensitivity and Specificity; Tumor Suppressor Proteins; Whole Exome Sequencing

Complex mosaic structural variations in human fetal brains. - Sekar, Shobana; Tomasini, Livia; Proukakis, Christos; Bae, Taejeong; Manlove, Logan; Jang, Yeongjun; Scuderi, Soraya; Zhou, Bo; Kalyva, Maria; Amiri, Anahita; Mariani, Jessica; Sedlazeck, Fritz J; et al. (Genome Res, 2020)
Somatic mosaicism, manifesting as single nucleotide variants (SNVs), mobile element insertions, and structural changes in the DNA, is a common phenomenon in human brain cells, with potential functional consequences. Using a clonal approach, we previously detected 200-400 mosaic SNVs per cell in three human fetal brains (15-21 wk postconception). However, structural variation in the human fetal brain has not yet been investigated. Here, we discover and validate four mosaic structural variants (SVs) in the same brains and resolve their precise breakpoints. The SVs were of kilobase scale and complex, consisting of deletion(s) and rearranged genomic fragments, which sometimes originated from different chromosomes. Sequences at the breakpoints of these rearrangements had microhomologies, suggesting their origin from replication errors. One SV was found in two clones, and we timed its origin to ∼14 wk postconception. No large scale mosaic copy number variants (CNVs) were detectable in normal fetal human brains, suggesting that previously reported megabase-scale CNVs in neurons arise at later stages of development. By reanalysis of public single nuclei data from adult brain neurons, we detected an extrachromosomal circular DNA event. Our study reveals the existence of mosaic SVs in the developing human brain, likely arising from cell proliferation during mid-neurogenesis. Although relatively rare compared to SNVs and present in ∼10% of neurons, SVs in developing human brain affect a comparable number of bases in the genome (∼6200 vs. ∼4000 bp), implying that they may have similar functional consequences.

Congenital diaphragmatic hernia as a prominent feature of a SPECC1L-related syndrome. - Wild, K Taylor; Gordon, Tia; Bhoj, Elizabeth J; Du, Haowei; Jhangiani, Shalini N; Posey, Jennifer E; Lupski, James R; Scott, Daryl A; Zackai, Elaine H (Am J Med Genet A, 2020)
Congenital diaphragmatic hernias (CDH) confer substantial morbidity and mortality. Genetic defects, including chromosomal anomalies, copy number variants, and sequence variants are identified in ~30% of patients with CDH. A genetic etiology is not yet found in 70% of patients, however there is a growing number of genetic syndromes and single gene disorders associated with CDH. While there have been two reported individuals with X-linked Opitz G/BBB syndrome with MID1 mutations who have CDH as an associated feature, CDH appears to be a much more prominent feature of a SPECC1L-related autosomal dominant Opitz G/BBB syndrome. Features unique to autosomal dominant Opitz G/BBB syndrome include branchial fistulae, omphalocele, and a bicornuate uterus. Here we present one new individual and five previously reported individuals with CDH found to have SPECC1L mutations. These cases provide strong evidence that SPECC1L is a bona fide CDH gene. We conclude that a SPECC1L-related Opitz G/BBB syndrome should be considered in any patient with CDH who has additional features of hypertelorism, a prominent forehead, a broad nasal bridge, anteverted nares, cleft lip/palate, branchial fistulae, omphalocele, and/or bicornuate uterus.

Congenital Heart Defects Due to Missense Variants. - Morton, Sarah U; Agarwal, Radhika; Madden, Jill A; Genetti, Casie A; Brownstein, Catherine A; López-Giráldez, Francesc; Choi, Jungmin; Seidman, Christine E; Seidman, Jonathan G; Lyon, Gholson J; Agrawal, Pankaj B (Circ Genom Precis Med, 2020)

Congenital myasthenic syndrome with mild intellectual disability caused by a recurrent SLC25A1 variant. - Balaraju, Sunitha; Topf, Ana; McMacken, Grace; Kumar, Veeramani Preethish; Pechmann, Astrid; Roper, Helen; Vengalil, Seena; Polavarapu, Kiran; Nashi, Saraswati; MAHjan, Niranjan Prakash; Barbosa, Ines A; Deshpande, Charu; et al. (Eur J Hum Genet, 2020)
Congenital myasthenic syndromes (CMS) are a clinically and genetically heterogeneous group of disorders caused by mutations which lead to impaired neuromuscular transmission. SLC25A1 encodes a mitochondrial citrate carrier, associated mainly with the severe neurometabolic disease combined D-2- and L-2-hydroxyglutaric aciduria (D/L-2-HGA). We previously reported a single family with a homozygous missense variant in SLC25A1 with a phenotype restricted to relatively mild CMS with intellectual disability, but to date no additional cases of this CMS subtype had been reported. Here, we performed whole exome sequencing (WES) in three additional and unrelated families presenting with CMS and mild intellectual disability to identify the underlying causative gene. The WES analysis revealed the presence of a homozygous c.740G>A; p.(Arg247Gln) missense SLC25A1 variant, the same SLC25A1 variant as identified in the original family with this phenotype. Electron microscopy of muscle from two cases revealed enlarged and accumulated mitochondria. Haplotype analysis performed in two unrelated families suggested that this variant is a result of recurrent mutation and not a founder effect. This suggests that p.(Arg247Gln) is associated with a relatively mild CMS phenotype with subtle mitochondrial abnormalities, while other variants in this gene cause more severe neurometabolic disease. In conclusion, the p.(Arg247Gln) SLC25A1 variant should be considered in patients presenting with a presynaptic CMS phenotype, particularly with accompanying intellectual disability.
Keywords: Adult; Female; Haplotypes; Homozygote; Humans; Intellectual Disability; Male; Mitochondrial Proteins; Muscle, Skeletal; Mutation, Missense; Myasthenic Syndromes, Congenital; Organic Anion Transporters

Copy number variants and fixed duplications among 198 rhesus macaques (Macaca mulatta). - Brasó-Vives, Marina; Povolotskaya, Inna S; Hartasánchez, Diego A; Farré, Xavier; Fernandez-Callejo, Marcos; Raveendran, Muthuswamy; Harris, R Alan; Rosene, Douglas L; Lorente-Galdos, Belen; Navarro, Arcadi; Marques-Bonet, Tomas; Rogers, Jeffrey; et al. (PLoS Genet, 2020)
The rhesus macaque is an abundant species of Old World monkeys and a valuable model organism for biomedical research due to its close phylogenetic relationship to humans. Copy number variation is one of the main sources of genomic diversity within and between species and a widely recognized cause of inter-individual differences in disease risk. However, copy number differences among rhesus macaques and between the human and macaque genomes, as well as the relevance of this diversity to research involving this nonhuman primate, remain understudied. Here we present a high-resolution map of sequence copy number for the rhesus macaque genome constructed from a dataset of 198 individuals. Our results show that about one-eighth of the rhesus macaque reference genome is composed of recently duplicated regions, either copy number variable regions or fixed duplications. Comparison with human genomic copy number maps based on previously published data shows that, despite overall similarities in the genome-wide distribution of these regions, there are specific differences at the chromosome level. Some of these create differences in the copy number profile between human disease genes and their rhesus macaque orthologs. Our results highlight the importance of addressing the number of copies of target genes in the design of experiments and cautions against human-centered assumptions in research conducted with model organisms. Overall, we present a genome-wide copy number map from a large sample of rhesus macaque individuals representing an important novel contribution concerning the evolution of copy number in primate genomes.
Keywords: Animals; Chromosome Mapping; DNA Copy Number Variations; Female; Gene Duplication; Genetics, Population; Genome; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Open Reading Frames; Phylogeny; Sequence Analysis, DNA; Species Specificity

Craniofacial phenotypes associated with Robinow syndrome. - Conlon, Christopher J; Abu-Ghname, Amjed; Raghuram, Anjali C; Davis, Matthew J; Guillen, Diana E; Sutton, V Reid; Carvalho, Claudia M B; Maricevich, Renata S (Am J Med Genet A, 2020)
Robinow syndrome is characterized by mesomelic limb shortening, hemivertebrae, and genital hypoplasia. Due to low prevalence and considerable phenotypic variability, it has been challenging to definitively characterize features of Robinow syndrome. While craniofacial abnormalities associated with Robinow syndrome have been broadly described, there is a lack of detailed descriptions of genotype-specific phenotypic craniofacial features. Patients with Robinow syndrome were invited for a multidisciplinary evaluation conducted by specialist physicians at our institution. A focused assessment of the craniofacial manifestations was performed by a single expert examiner using clinical examination and standard photographic images. A total of 13 patients with clinical and molecular diagnoses consistent with either dominant Robinow syndrome (DRS) or recessive Robinow syndrome (RRS) were evaluated. On craniofacial examination, gingival hyperplasia was nearly ubiquitous in all patients. Orbital hypertelorism, a short nose with anteverted and flared nares, a triangular mouth with a long philtrum, cleft palate, macrocephaly, and frontal bossing were not observed in all individuals but affected individuals with both DRS and RRS. Other anomalies were more selective in their distribution in this patient cohort. We present a comprehensive analysis of the craniofacial findings in patients with Robinow Syndrome, describing associated morphological features and correlating phenotypic manifestations to underlying genotype in a manner relevant for early recognition and focused evaluation of these patients.

Cytoplasmic "ciliary inclusions" in isolation are not sufficient for the diagnosis of primary ciliary dyskinesia. - Vece, Timothy J; Sagel, Scott D; Zariwala, Maimoona A; Sullivan, Kelli M; Burns, Kimberlie A; Dutcher, Susan K; Yusupov, Roman; Leigh, Margaret W; Knowles, Michael R (Pediatr Pulmonol, 2020)
BACKGROUND: The diagnosis of primary ciliary dyskinesia (PCD) is difficult and requires a combination of clinical features, nasal nitric oxide testing, cilia ultrastructural analysis by electron microscopy (EM), and genetics. A recently described cytoplasmic ultrastructural change termed "ciliary inclusions" was reported to be diagnostic of PCD; however, no supporting evidence of PCD was provided. In this study, we sought to confirm, or refute, the diagnosis of PCD in subjects with "ciliary inclusions" on EM. METHODS: Six subjects from five families with previous lab reports of "ciliary inclusions" on EMs of ciliated cells were identified and evaluated at a Genetic Disorders of Mucociliary Clearance Consortium site. We performed a detailed clinical history, nasal nitric oxide measurement, genetic testing including whole-exome sequencing (WES), and when possible, repeat ciliary EM study. RESULTS: Only one of six subjects had multiple and persistent clinical features congruent with PCD. No subject had situs inversus. Only one of six subjects had a very low nasal nitric oxide level. No "ciliary inclusions" were found in three subjects who had a repeat ciliary EM, and ciliary axonemal ultrastructures were normal. Genetic testing, including WES, was negative for PCD-causing genes, and for pathogenic variants in gene pathways that might cause "ciliary inclusions," such as ciliary biogenesis. CONCLUSION: "Ciliary Inclusions", in isolation, are not sufficient to diagnosis PCD. If seen, additional studies should be done to pursue an accurate diagnosis.
Keywords: Child, Preschool; Cilia; Ciliary Motility Disorders; Female; Genetic Testing; Humans; Infant; Male; Nasal Mucosa; Nitric Oxide; Whole Exome Sequencing

DAAM2 Variants Cause Nephrotic Syndrome via Actin Dysregulation. - Schneider, Ronen; Deutsch, Konstantin; Hoeprich, Gregory J; Marquez, Jonathan; Hermle, Tobias; Braun, Daniela A; Seltzsam, Steve; Kitzler, Thomas M; Mao, Youying; Buerger, Florian; Majmundar, Amar J; Onuchic-Whitford, Ana C; et al. (Am J Hum Genet, 2020)
The discovery of >60 monogenic causes of nephrotic syndrome (NS) has revealed a central role for the actin regulators RhoA/Rac1/Cdc42 and their effectors, including the formin INF2. By whole-exome sequencing (WES), we here discovered bi-allelic variants in the formin DAAM2 in four unrelated families with steroid-resistant NS. We show that DAAM2 localizes to the cytoplasm in podocytes and in kidney sections. Further, the variants impair DAAM2-dependent actin remodeling processes: wild-type DAAM2 cDNA, but not cDNA representing missense variants found in individuals with NS, rescued reduced podocyte migration rate (PMR) and restored reduced filopodia formation in shRNA-induced DAAM2-knockdown podocytes. Filopodia restoration was also induced by the formin-activating molecule IMM-01. DAAM2 also co-localizes and co-immunoprecipitates with INF2, which is intriguing since variants in both formins cause NS. Using in vitro bulk and TIRF microscopy assays, we find that DAAM2 variants alter actin assembly activities of the formin. In a Xenopus daam2-CRISPR knockout model, we demonstrate actin dysregulation in vivo and glomerular maldevelopment that is rescued by WT-DAAM2 mRNA. We conclude that DAAM2 variants are a likely cause of monogenic human SRNS due to actin dysregulation in podocytes. Further, we provide evidence that DAAM2-associated SRNS may be amenable to treatment using actin regulating compounds.
Keywords: Actins; Alleles; Animals; Animals, Genetically Modified; Cell Movement; Cytoplasm; Formins; Genetic Variation; Humans; Kidney; Kidney Glomerulus; Microfilament Proteins; Mutation, Missense; Nephrotic Syndrome; Podocytes; Pseudopodia; rho GTP-Binding Proteins; RNA, Small Interfering; Whole Exome Sequencing; Xenopus

dbMTS: A comprehensive database of putative human microRNA target site SNVs and their functional predictions. - Li, Chang; Mou, Chengcheng; Swartz, Michael D; Yu, Bing; Bai, Yongsheng; Tu, Yicheng; Liu, Xiaoming (Hum Mutat, 2020)
MicroRNAs (miRNA) are short noncoding RNAs that can repress the expression of protein-coding messenger RNAs (mRNAs) by binding to the 3'-untranslated region (UTR) of the target. Genetic mutations such as single nucleotide variants (SNVs) in the 3'-UTR of the mRNAs can disrupt miRNA regulation. In this study, we presented dbMTS, a database for miRNA target site (MTS) SNVs and their functional annotations. This database can help studies easily identify putative SNVs that affect miRNA targeting and facilitate the prioritization of their functional importance. dbMTS is freely available for academic use at http://database.liulab.science/dbMTS as a web service or a downloadable attached database of dbNSFP.

De novo and inherited variants in ZNF292 underlie a neurodevelopmental disorder with features of autism spectrum disorder. - Mirzaa, Ghayda M; Chong, Jessica X; Piton, Amélie; Popp, Bernt; Foss, Kimberly; Guo, Hui; Harripaul, Ricardo; Xia, Kun; Scheck, Joshua; Aldinger, Kimberly A; Sajan, Samin A; Tang, Sha; et al. (Genet Med, 2020)
PURPOSE: Intellectual disability (ID) and autism spectrum disorder (ASD) are genetically heterogeneous neurodevelopmental disorders. We sought to delineate the clinical, molecular, and neuroimaging spectrum of a novel neurodevelopmental disorder caused by variants in the zinc finger protein 292 gene (ZNF292). METHODS: We ascertained a cohort of 28 families with ID due to putatively pathogenic ZNF292 variants that were identified via targeted and exome sequencing. Available data were analyzed to characterize the canonical phenotype and examine genotype-phenotype relationships. RESULTS: Probands presented with ID as well as a spectrum of neurodevelopmental features including ASD, among others. All ZNF292 variants were de novo, except in one family with dominant inheritance. ZNF292 encodes a highly conserved zinc finger protein that acts as a transcription factor and is highly expressed in the developing human brain supporting its critical role in neurodevelopment. CONCLUSION: De novo and dominantly inherited variants in ZNF292 are associated with a range of neurodevelopmental features including ID and ASD. The clinical spectrum is broad, and most individuals present with mild to moderate ID with or without other syndromic features. Our results suggest that variants in ZNF292 are likely a recurrent cause of a neurodevelopmental disorder manifesting as ID with or without ASD.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Nerve Tissue Proteins; Neurodevelopmental Disorders; Neuroimaging; Whole Exome Sequencing

De Novo Damaging Variants, Clinical Phenotypes, and Post-Operative Outcomes in Congenital Heart Disease. - Boskovski, Marko T; Homsy, Jason; Nathan, Meena; Sleeper, Lynn A; Morton, Sarah; Manheimer, Kathryn B; Tai, Angela; Gorham, Joshua; Lewis, Matthew; Swartz, Michael; Alfieris, George M; Bacha, Emile A; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: De novo genic and copy number variants are enriched in patients with congenital heart disease, particularly those with extra-cardiac anomalies. The impact of de novo damaging variants on outcomes following cardiac repair is unknown. METHODS: We studied 2517 patients with congenital heart disease who had undergone whole-exome sequencing as part of the CHD GENES study (Congenital Heart Disease Genetic Network). RESULTS: Two hundred ninety-four patients (11.7%) had clinically significant de novo variants. Patients with de novo damaging variants were 2.4 times more likely to have extra-cardiac anomalies (=5.63×10). In 1268 patients (50.4%) who had surgical data available and underwent open-heart surgery exclusive of heart transplantation as their first operation, we analyzed transplant-free survival following the first operation. Median follow-up was 2.65 years. De novo variants were associated with worse transplant-free survival (hazard ratio, 3.51; =5.33×10) and longer times to final extubation (hazard ratio, 0.74; =0.005). As de novo variants had a significant interaction with extra-cardiac anomalies for transplant-free survival (=0.003), de novo variants conveyed no additional risk for transplant-free survival for patients with these anomalies (adjusted hazard ratio, 1.96; =0.06). By contrast, de novo variants in patients without extra-cardiac anomalies were associated with worse transplant-free survival during follow-up (hazard ratio, 11.21; =1.61×10) than that of patients with no de novo variants. Using agnostic machine-learning algorithms, we identified de novo copy number variants at 15q25.2 and 15q11.2 as being associated with worse transplant-free survival and 15q25.2, 22q11.21, and 3p25.2 as being associated with prolonged time to final extubation. CONCLUSIONS: In patients with congenital heart disease undergoing open-heart surgery, de novo variants were associated with worse transplant-free survival and longer times on the ventilator. De novo variants were most strongly associated with adverse outcomes among patients without extra-cardiac anomalies, suggesting a benefit for preoperative genetic testing even when genetic abnormalities are not suspected during routine clinical practice. Registration: URL: https://www.clinicaltrials.gov. Unique identifier: NCT01196182.

De novo EIF2AK1 and EIF2AK2 Variants Are Associated with Developmental Delay, Leukoencephalopathy, and Neurologic Decompensation. - Mao, Dongxue; Reuter, Chloe M; Ruzhnikov, Maura R Z; Beck, Anita E; Farrow, Emily G; Emrick, Lisa T; Rosenfeld, Jill A; Mackenzie, Katherine M; Robak, Laurie; Wheeler, Matthew T; Burrage, Lindsay C; Jain, Mahim; et al. (Am J Hum Genet, 2020)
EIF2AK1 and EIF2AK2 encode members of the eukaryotic translation initiation factor 2 alpha kinase (EIF2AK) family that inhibits protein synthesis in response to physiologic stress conditions. EIF2AK2 is also involved in innate immune response and the regulation of signal transduction, apoptosis, cell proliferation, and differentiation. Despite these findings, human disorders associated with deleterious variants in EIF2AK1 and EIF2AK2 have not been reported. Here, we describe the identification of nine unrelated individuals with heterozygous de novo missense variants in EIF2AK1 (1/9) or EIF2AK2 (8/9). Features seen in these nine individuals include white matter alterations (9/9), developmental delay (9/9), impaired language (9/9), cognitive impairment (8/9), ataxia (6/9), dysarthria in probands with verbal ability (6/9), hypotonia (7/9), hypertonia (6/9), and involuntary movements (3/9). Individuals with EIF2AK2 variants also exhibit neurological regression in the setting of febrile illness or infection. We use mammalian cell lines and proband-derived fibroblasts to further confirm the pathogenicity of variants in these genes and found reduced kinase activity. EIF2AKs phosphorylate eukaryotic translation initiation factor 2 subunit 1 (EIF2S1, also known as EIF2α), which then inhibits EIF2B activity. Deleterious variants in genes encoding EIF2B proteins cause childhood ataxia with central nervous system hypomyelination/vanishing white matter (CACH/VWM), a leukodystrophy characterized by neurologic regression in the setting of febrile illness and other stressors. Our findings indicate that EIF2AK2 missense variants cause a neurodevelopmental syndrome that may share phenotypic and pathogenic mechanisms with CACH/VWM.
Keywords: Adolescent; Ataxia; Child; Child, Preschool; Developmental Disabilities; eIF-2 Kinase; Female; Genetic Variation; Hereditary Central Nervous System Demyelinating Diseases; Humans; Infant; Leukoencephalopathies; Male; Nervous System Malformations; White Matter

Deciphering congenital anomalies for the next generation. - Wojcik, Monica H; Agrawal, Pankaj B (Cold Spring Harb Mol Case Stud, 2020)
Congenital anomalies are common, with 2%-3% of infants estimated to have at least one major congenital malformation and countless others with minor malformations of lesser cosmetic or medical importance. As congenital malformations are major drivers of morbidity and mortality, representing the leading cause of infant mortality in the United States, there is substantial interest in understanding the underlying etiologies-particularly if modifiable causes may be identified or pre- or postnatal treatments can be offered. Recent research has begun to reveal the spectrum of monogenic disorders that commonly result in birth defects, and newer approaches have revealed non-Mendelian genetic contributions including gene-environment interactions. Our experience suggests that increased efforts to sequence and analyze cases of perinatal death, as well as continued global collaboration, will be essential in understanding the genomic landscape of structural anomalies.
Keywords: Congenital Abnormalities; Family Characteristics; Female; Humans; Infant; Pregnancy

Defective glycosylation and multisystem abnormalities characterize the primary immunodeficiency XMEN disease. - Ravell, Juan C; Matsuda-Lennikov, Mami; Chauvin, Samuel D; Zou, Juan; Biancalana, Matthew; Deeb, Sally J; Price, Susan; Su, Helen C; Notarangelo, Giulia; Jiang, Ping; Morawski, Aaron; Kanellopoulou, Chrysi; et al. (J Clin Invest, 2020)
X-linked immunodeficiency with magnesium defect, EBV infection, and neoplasia (XMEN) disease are caused by deficiency of the magnesium transporter 1 (MAGT1) gene. We studied 23 patients with XMEN, 8 of whom were EBV naive. We observed lymphadenopathy (LAD), cytopenias, liver disease, cavum septum pellucidum (CSP), and increased CD4-CD8-B220-TCRαβ+ T cells (αβDNTs), in addition to the previously described features of an inverted CD4/CD8 ratio, CD4+ T lymphocytopenia, increased B cells, dysgammaglobulinemia, and decreased expression of the natural killer group 2, member D (NKG2D) receptor. EBV-associated B cell malignancies occurred frequently in EBV-infected patients. We studied patients with XMEN and patients with autoimmune lymphoproliferative syndrome (ALPS) by deep immunophenotyping (32 immune markers) using time-of-flight mass cytometry (CyTOF). Our analysis revealed that the abundance of 2 populations of naive B cells (CD20+CD27-CD22+IgM+HLA-DR+CXCR5+CXCR4++CD10+CD38+ and CD20+CD27-CD22+IgM+HLA-DR+CXCR5+CXCR4+CD10-CD38-) could differentially classify XMEN, ALPS, and healthy individuals. We also performed glycoproteomics analysis on T lymphocytes and show that XMEN disease is a congenital disorder of glycosylation that affects a restricted subset of glycoproteins. Transfection of MAGT1 mRNA enabled us to rescue proteins with defective glycosylation. Together, these data provide new clinical and pathophysiological foundations with important ramifications for the diagnosis and treatment of XMEN disease.
Keywords: Antigens, CD; Autoimmune Lymphoproliferative Syndrome; Cation Transport Proteins; CD4-CD8 Ratio; Female; Glycosylation; Humans; Magnesium Deficiency; Male; X-Linked Combined Immunodeficiency Diseases

Deficiencies in vesicular transport mediated by TRAPPC4 are associated with severe syndromic intellectual disability. - Van Bergen, Nicole J; Guo, Yiran; Al-Deri, Noraldin; Lipatova, Zhanna; Stanga, Daniela; Zhao, Sarah; Murtazina, Rakhilya; Gyurkovska, Valeriya; Pehlivan, Davut; Mitani, Tadahiro; Gezdirici, Alper; Antony, Jayne; et al. (Brain, 2020)
The conserved transport protein particle (TRAPP) complexes regulate key trafficking events and are required for autophagy. TRAPPC4, like its yeast Trs23 orthologue, is a core component of the TRAPP complexes and one of the essential subunits for guanine nucleotide exchange factor activity for Rab1 GTPase. Pathogenic variants in specific TRAPP subunits are associated with neurological disorders. We undertook exome sequencing in three unrelated families of Caucasian, Turkish and French-Canadian ethnicities with seven affected children that showed features of early-onset seizures, developmental delay, microcephaly, sensorineural deafness, spastic quadriparesis and progressive cortical and cerebellar atrophy in an effort to determine the genetic aetiology underlying neurodevelopmental disorders. All seven affected subjects shared the same identical rare, homozygous, potentially pathogenic variant in a non-canonical, well-conserved splice site within TRAPPC4 (hg19:chr11:g.118890966A>G; TRAPPC4: NM_016146.5; c.454+3A>G). Single nucleotide polymorphism array analysis revealed there was no haplotype shared between the tested Turkish and Caucasian families suggestive of a variant hotspot region rather than a founder effect. In silico analysis predicted the variant to cause aberrant splicing. Consistent with this, experimental evidence showed both a reduction in full-length transcript levels and an increase in levels of a shorter transcript missing exon 3, suggestive of an incompletely penetrant splice defect. TRAPPC4 protein levels were significantly reduced whilst levels of other TRAPP complex subunits remained unaffected. Native polyacrylamide gel electrophoresis and size exclusion chromatography demonstrated a defect in TRAPP complex assembly and/or stability. Intracellular trafficking through the Golgi using the marker protein VSVG-GFP-ts045 demonstrated significantly delayed entry into and exit from the Golgi in fibroblasts derived from one of the affected subjects. Lentiviral expression of wild-type TRAPPC4 in these fibroblasts restored trafficking, suggesting that the trafficking defect was due to reduced TRAPPC4 levels. Consistent with the recent association of the TRAPP complex with autophagy, we found that the fibroblasts had a basal autophagy defect and a delay in autophagic flux, possibly due to unsealed autophagosomes. These results were validated using a yeast trs23 temperature sensitive variant that exhibits constitutive and stress-induced autophagic defects at permissive temperature and a secretory defect at restrictive temperature. In summary we provide strong evidence for pathogenicity of this variant in a member of the core TRAPP subunit, TRAPPC4 that associates with vesicular trafficking and autophagy defects. This is the first report of a TRAPPC4 variant, and our findings add to the growing number of TRAPP-associated neurological disorders.
Keywords: Atrophy; Autophagy; Cerebellum; Cerebral Cortex; Child; Child, Preschool; Craniofacial Abnormalities; Deafness; Developmental Disabilities; Epilepsy; Female; Fibroblasts; Hearing Loss, Sensorineural; Humans; Infant; Infant, Newborn; Intellectual Disability; Male; Microcephaly; Microscopy, Fluorescence; Muscle Spasticity; Nerve Tissue Proteins; Neurodevelopmental Disorders; Pedigree; Quadriplegia; RNA Splice Sites; Syndrome; Vesicular Transport Proteins

Delineation of a Human Mendelian Disorder of the DNA Demethylation Machinery: TET3 Deficiency. - Beck, David B; Petracovici, Ana; He, Chongsheng; Moore, Hannah W; Louie, Raymond J; Ansar, Muhammad; Douzgou, Sofia; Sithambaram, Sivagamy; Cottrell, Trudie; Santos-Cortez, Regie Lyn P; Prijoles, Eloise J; Bend, Renee; et al. (Am J Hum Genet, 2020)
Germline pathogenic variants in chromatin-modifying enzymes are a common cause of pediatric developmental disorders. These enzymes catalyze reactions that regulate epigenetic inheritance via histone post-translational modifications and DNA methylation. Cytosine methylation (5-methylcytosine [5mC]) of DNA is the quintessential epigenetic mark, yet no human Mendelian disorder of DNA demethylation has yet been delineated. Here, we describe in detail a Mendelian disorder caused by the disruption of DNA demethylation. TET3 is a methylcytosine dioxygenase that initiates DNA demethylation during early zygote formation, embryogenesis, and neuronal differentiation and is intolerant to haploinsufficiency in mice and humans. We identify and characterize 11 cases of human TET3 deficiency in eight families with the common phenotypic features of intellectual disability and/or global developmental delay; hypotonia; autistic traits; movement disorders; growth abnormalities; and facial dysmorphism. Mono-allelic frameshift and nonsense variants in TET3 occur throughout the coding region. Mono-allelic and bi-allelic missense variants localize to conserved residues; all but one such variant occur within the catalytic domain, and most display hypomorphic function in an assay of catalytic activity. TET3 deficiency and other Mendelian disorders of the epigenetic machinery show substantial phenotypic overlap, including features of intellectual disability and abnormal growth, underscoring shared disease mechanisms.
Keywords: Adult; Amino Acid Sequence; Autistic Disorder; Child; Child, Preschool; Developmental Disabilities; Dioxygenases; DNA Demethylation; Embryonic Development; Female; Gene Expression Regulation, Developmental; Growth Disorders; Humans; Infant; Male; Middle Aged; Movement Disorders; Pedigree; Protein Conformation; Sequence Homology; Young Adult

Determinants of telomere length across human tissues. - Demanelis, Kathryn; Jasmine, Farzana; Chen, Lin S; Chernoff, Meytal; Tong, Lin; Delgado, Dayana; Zhang, Chenan; Shinkle, Justin; Sabarinathan, Mekala; Lin, Hannah; Ramirez, Eduardo; Oliva, Meritxell; et al. (Science, 2020)
Telomere shortening is a hallmark of aging. Telomere length (TL) in blood cells has been studied extensively as a biomarker of human aging and disease; however, little is known regarding variability in TL in nonblood, disease-relevant tissue types. Here, we characterize variability in TLs from 6391 tissue samples, representing >20 tissue types and 952 individuals from the Genotype-Tissue Expression (GTEx) project. We describe differences across tissue types, positive correlation among tissue types, and associations with age and ancestry. We show that genetic variation affects TL in multiple tissue types and that TL may mediate the effect of age on gene expression. Our results provide the foundational knowledge regarding TL in healthy tissues that is needed to interpret epidemiological studies of TL and human health.
Keywords: Aging; Genetic Markers; Genetic Variation; Humans; Organ Specificity; Telomere; Telomere Homeostasis; Telomere Shortening

Development and validation of the VISAGE AmpliSeq basic tool to predict appearance and ancestry from DNA. - Xavier, Catarina; de la Puente, Maria; Mosquera-Miguel, Ana; Freire-Aradas, Ana; Kalamara, Vivian; Vidaki, Athina; E Gross, Theresa; Revoir, Andrew; Pośpiech, Ewelina; Kartasińska, Ewa; Spólnicka, Magdalena; Branicki, Wojciech; et al. (Forensic Sci Int Genet, 2020)
Forensic DNA phenotyping is gaining interest as the number of applications increases within the forensic genetics community. The possibility of providing investigative leads in addition to conventional DNA profiling for human identification provides new insights into otherwise "cold" police investigations. The ability of reporting on the bio-geographical ancestry (BGA), appearance characteristics and age based on DNA obtained from a crime scene sample of an unknown donor makes the exploration of such markers and the development of new methods meaningful for criminal investigations. The VISible Attributes through GEnomics (VISAGE) Consortium aims to disseminate and broaden the use of predictive markers and develop fully optimized and validated prototypes for forensic casework implementation. Here, the first VISAGE appearance and ancestry tool development, performance and validation is reported. A total of 153 SNPs (96.84 % assay conversion rate) were successfully incorporated into a single multiplex reaction using the AmpliSeq™ design pipeline, and applied for massively parallel sequencing with the Ion S5 platform. A collaborative effort involving six VISAGE laboratory partners was devised to perform all validation tests. An extensive validation plan was carefully organized to explore the assay's overall performance with optimum and low-input samples, as well as with challenging and casework mock samples. In addition, forensic validation studies such as concordance and mixture tests recurring to the Coriell sample set with known genotypes were performed. Finally, inhibitor tolerance and specificity were also evaluated. Results showed a robust, highly sensitive assay with good overall concordance between laboratories.

A diagnostic ceiling for exome sequencing in cerebellar ataxia and related neurological disorders. - Ngo, Kathie J; Rexach, Jessica E; Lee, Hane; Petty, Lauren E; Perlman, Susan; Valera, Juliana M; Deignan, Joshua L; Mao, Yuanming; Aker, Mamdouh; Posey, Jennifer E; Jhangiani, Shalini N; Coban-Akdemir, Zeynep H; et al. (Hum Mutat, 2020)
Genetic ataxias are associated with mutations in hundreds of genes with high phenotypic overlap complicating the clinical diagnosis. Whole-exome sequencing (WES) has increased the overall diagnostic rate considerably. However, the upper limit of this method remains ill-defined, hindering efforts to address the remaining diagnostic gap. To further assess the role of rare coding variation in ataxic disorders, we reanalyzed our previously published exome cohort of 76 predominantly adult and sporadic-onset patients, expanded the total number of cases to 260, and introduced analyses for copy number variation and repeat expansion in a representative subset. For new cases (n = 184), our resulting clinically relevant detection rate remained stable at 47% with 24% classified as pathogenic. Reanalysis of the previously sequenced 76 patients modestly improved the pathogenic rate by 7%. For the combined cohort (n = 260), the total observed clinical detection rate was 52% with 25% classified as pathogenic. Published studies of similar neurological phenotypes report comparable rates. This consistency across multiple cohorts suggests that, despite continued technical and analytical advancements, an approximately 50% diagnostic rate marks a relative ceiling for current WES-based methods and a more comprehensive genome-wide assessment is needed to identify the missing causative genetic etiologies for cerebellar ataxia and related neurodegenerative diseases.

Discovery and population genomics of structural variation in a songbird genus. - Weissensteiner, Matthias H; Bunikis, Ignas; Catalán, Ana; Francoijs, Kees-Jan; Knief, Ulrich; Heim, Wieland; Peona, Valentina; Pophaly, Saurabh D; Sedlazeck, Fritz J; Suh, Alexander; Warmuth, Vera M; Wolf, Jochen B W (Nat Commun, 2020)
Structural variation (SV) constitutes an important type of genetic mutations providing the raw material for evolution. Here, we uncover the genome-wide spectrum of intra- and interspecific SV segregating in natural populations of seven songbird species in the genus Corvus. Combining short-read (N = 127) and long-read re-sequencing (N = 31), as well as optical mapping (N = 16), we apply both assembly- and read mapping approaches to detect SV and characterize a total of 220,452 insertions, deletions and inversions. We exploit sampling across wide phylogenetic timescales to validate SV genotypes and assess the contribution of SV to evolutionary processes in an avian model of incipient speciation. We reveal an evolutionary young (~530,000 years) cis-acting 2.25-kb LTR retrotransposon insertion reducing expression of the NDP gene with consequences for premating isolation. Our results attest to the wealth and evolutionary significance of SV segregating in natural populations and highlight the need for reliable SV genotyping.
Keywords: Animals; Chromosome Inversion; Gene Deletion; Genetic Variation; Genetics, Population; Genome; Genomic Structural Variation; Genotype; Phylogeny; Polymorphism, Single Nucleotide; Retroelements; Sequence Analysis, DNA; Songbirds

Disease-associated CTNNBL1 mutation impairs somatic hypermutation by decreasing nuclear AID. - Kuhny, Marcel; Forbes, Lisa R; Çakan, Elif; Vega-Loza, Andrea; Kostiuk, Valentyna; Dinesh, Ravi K; Glauzy, Salomé; Stray-Pedersen, Asbjorg; Pezzi, Ashley E; Hanson, I Celine; Vargas-Hernandez, Alexander; Xu, Mina LuQuing; et al. (J Clin Invest, 2020)
Patients with common variable immunodeficiency associated with autoimmune cytopenia (CVID+AIC) generate few isotype-switched B cells with severely decreased frequencies of somatic hypermutations (SHMs), but their underlying molecular defects remain poorly characterized. We identified a CVID+AIC patient who displays a rare homozygous missense M466V mutation in β-catenin-like protein 1 (CTNNBL1). Because CTNNBL1 binds activation-induced cytidine deaminase (AID) that catalyzes SHM, we tested AID interactions with the CTNNBL1 M466V variant. We found that the M466V mutation interfered with the association of CTNNBL1 with AID, resulting in decreased AID in the nuclei of patient EBV-transformed B cell lines and of CTNNBL1 466V/V Ramos B cells engineered to express only CTNNBL1 M466V using CRISPR/Cas9 technology. As a consequence, the scarce IgG+ memory B cells from the CTNNBL1 466V/V patient showed a low SHM frequency that averaged 6.7 mutations compared with about 18 mutations per clone in healthy-donor counterparts. In addition, CTNNBL1 466V/V Ramos B cells displayed a decreased incidence of SHM that was reduced by half compared with parental WT Ramos B cells, demonstrating that the CTNNBL1 M466V mutation is responsible for defective SHM induction. We conclude that CTNNBL1 plays an important role in regulating AID-dependent antibody diversification in humans.
Keywords: Amino Acid Substitution; Apoptosis Regulatory Proteins; B-Lymphocytes; Cell Line; Child, Preschool; Common Variable Immunodeficiency; Cytidine Deaminase; Female; Homozygote; Humans; Immunologic Memory; Mutation, Missense; Nuclear Proteins; Somatic Hypermutation, Immunoglobulin

Distinct effects on mRNA export factor GANP underlie neurological disease phenotypes and alter gene expression depending on intron content. - Woldegebriel, Rosa; Kvist, Jouni; Andersson, Noora; Õunap, Katrin; Reinson, Karit; Wojcik, Monica H; Bijlsma, Emilia K; Hoffer, Mariette J V; Ryan, Monique M; Stark, Zornitza; Walsh, Maie; Cuppen, Inge; et al. (Hum Mol Genet, 2020)
Defects in the mRNA export scaffold protein GANP, encoded by the MCM3AP gene, cause autosomal recessive early-onset peripheral neuropathy with or without intellectual disability. We extend here the phenotypic range associated with MCM3AP variants, by describing a severely hypotonic child and a sibling pair with a progressive encephalopathic syndrome. In addition, our analysis of skin fibroblasts from affected individuals from seven unrelated families indicates that disease variants result in depletion of GANP except when they alter critical residues in the Sac3 mRNA binding domain. GANP depletion was associated with more severe phenotypes compared with the Sac3 variants. Patient fibroblasts showed transcriptome alterations that suggested intron content-dependent regulation of gene expression. For example, all differentially expressed intronless genes were downregulated, including ATXN7L3B, which couples mRNA export to transcription activation by association with the TREX-2 and SAGA complexes. Our results provide insight into the molecular basis behind genotype-phenotype correlations in MCM3AP-associated disease and suggest mechanisms by which GANP defects might alter RNA metabolism.

Dominant-negative mutations in human IL6ST underlie hyper-IgE syndrome. - Béziat, Vivien; Tavernier, Simon J; Chen, Yin-Huai; Ma, Cindy S; Materna, Marie; Laurence, Arian; Staal, Jens; Aschenbrenner, Dominik; Roels, Lisa; Worley, Lisa; Claes, Kathleen; Gartner, Lisa; et al. (J Exp Med, 2020)
Autosomal dominant hyper-IgE syndrome (AD-HIES) is typically caused by dominant-negative (DN) STAT3 mutations. Patients suffer from cold staphylococcal lesions and mucocutaneous candidiasis, severe allergy, and skeletal abnormalities. We report 12 patients from 8 unrelated kindreds with AD-HIES due to DN IL6ST mutations. We identified seven different truncating mutations, one of which was recurrent. The mutant alleles encode GP130 receptors bearing the transmembrane domain but lacking both the recycling motif and all four STAT3-recruiting tyrosine residues. Upon overexpression, the mutant proteins accumulate at the cell surface and are loss of function and DN for cellular responses to IL-6, IL-11, LIF, and OSM. Moreover, the patients' heterozygous leukocytes and fibroblasts respond poorly to IL-6 and IL-11. Consistently, patients with STAT3 and IL6ST mutations display infectious and allergic manifestations of IL-6R deficiency, and some of the skeletal abnormalities of IL-11R deficiency. DN STAT3 and IL6ST mutations thus appear to underlie clinical phenocopies through impairment of the IL-6 and IL-11 response pathways.
Keywords: Adolescent; Alleles; C-Reactive Protein; Cell Membrane; Cells, Cultured; Child; Cytokine Receptor gp130; Cytokines; Female; Fibroblasts; Genes, Dominant; Genetics, Population; HEK293 Cells; Humans; Job Syndrome; Kinetics; Loss of Function Mutation; Male; Middle Aged; Models, Biological; Mutation; Pedigree; Phenotype; Th2 Cells; Up-Regulation; Young Adult

Dysfunction of the ciliary ARMC9/TOGARAM1 protein module causes Joubert syndrome. - Latour, Brooke L; Van De Weghe, Julie C; Rusterholz, Tamara Ds; Letteboer, Stef Jf; Gomez, Arianna; Shaheen, Ranad; Gesemann, Matthias; Karamzade, Arezou; Asadollahi, Mostafa; Barroso-Gil, Miguel; Chitre, Manali; Grout, Megan E; et al. (J Clin Invest, 2020)
Joubert syndrome (JBTS) is a recessive neurodevelopmental ciliopathy characterized by a pathognomonic hindbrain malformation. All known JBTS genes encode proteins involved in the structure or function of primary cilia, ubiquitous antenna-like organelles essential for cellular signal transduction. Here, we used the recently identified JBTS-associated protein armadillo repeat motif-containing 9 (ARMC9) in tandem-affinity purification and yeast 2-hybrid screens to identify a ciliary module whose dysfunction underlies JBTS. In addition to the known JBTS-associated proteins CEP104 and CSPP1, we identified coiled-coil domain containing 66 (CCDC66) and TOG array regulator of axonemal microtubules 1 (TOGARAM1) as ARMC9 interaction partners. We found that TOGARAM1 variants cause JBTS and disrupt TOGARAM1 interaction with ARMC9. Using a combination of protein interaction analyses, characterization of patient-derived fibroblasts, and analysis of CRISPR/Cas9-engineered zebrafish and hTERT-RPE1 cells, we demonstrated that dysfunction of ARMC9 or TOGARAM1 resulted in short cilia with decreased axonemal acetylation and polyglutamylation, but relatively intact transition zone function. Aberrant serum-induced ciliary resorption and cold-induced depolymerization in ARMC9 and TOGARAM1 patient cell lines suggest a role for this new JBTS-associated protein module in ciliary stability.
Keywords: Abnormalities, Multiple; Acetylation; Animals; Armadillo Domain Proteins; Cerebellum; Cilia; CRISPR-Cas Systems; Disease Models, Animal; Eye Abnormalities; Humans; Kidney Diseases, Cystic; Peptides; Retina; Zebrafish; Zebrafish Proteins

Emerging Targets for Cardiovascular Disease Prevention in Diabetes. - Stitziel, Nathan O; Kanter, Jenny E; Bornfeldt, Karin E (Trends Mol Med, 2020)
Type 1 and type 2 diabetes mellitus (T1DM and T2DM) increase the risk of atherosclerotic cardiovascular disease (CVD), resulting in acute cardiovascular events, such as heart attack and stroke. Recent clinical trials point toward new treatment and prevention strategies for cardiovascular complications of T2DM. New antidiabetic agents show unexpected cardioprotective benefits. Moreover, genetic and reverse translational strategies have revealed potential novel targets for CVD prevention in diabetes, including inhibition of apolipoprotein C3 (APOC3). Modeling and pharmacology-based approaches to improve insulin action provide additional potential strategies to combat CVD. The development of new strategies for improved diabetes and lipid control fuels hope for future prevention of CVD associated with diabetes.

Epilepsy subtype-specific copy number burden observed in a genome-wide study of 17 458 subjects. - Niestroj, Lisa-Marie; Perez-Palma, Eduardo; Howrigan, Daniel P; Zhou, Yadi; Cheng, Feixiong; Saarentaus, Elmo; Nürnberg, Peter; Stevelink, Remi; Daly, Mark J; Palotie, Aarno; Lal, Dennis (Brain, 2020)
Cytogenic testing is routinely applied in most neurological centres for severe paediatric epilepsies. However, which characteristics of copy number variants (CNVs) confer most epilepsy risk and which epilepsy subtypes carry the most CNV burden, have not been explored on a genome-wide scale. Here, we present the largest CNV investigation in epilepsy to date with 10 712 European epilepsy cases and 6746 ancestry-matched controls. Patients with genetic generalized epilepsy, lesional focal epilepsy, non-acquired focal epilepsy, and developmental and epileptic encephalopathy were included. All samples were processed with the same technology and analysis pipeline. All investigated epilepsy types, including lesional focal epilepsy patients, showed an increase in CNV burden in at least one tested category compared to controls. However, we observed striking differences in CNV burden across epilepsy types and investigated CNV categories. Genetic generalized epilepsy patients have the highest CNV burden in all categories tested, followed by developmental and epileptic encephalopathy patients. Both epilepsy types also show association for deletions covering genes intolerant for truncating variants. Genome-wide CNV breakpoint association showed not only significant loci for genetic generalized and developmental and epileptic encephalopathy patients but also for lesional focal epilepsy patients. With a 34-fold risk for developing genetic generalized epilepsy, we show for the first time that the established epilepsy-associated 15q13.3 deletion represents the strongest risk CNV for genetic generalized epilepsy across the whole genome. Using the human interactome, we examined the largest connected component of the genes overlapped by CNVs in the four epilepsy types. We observed that genetic generalized epilepsy and non-acquired focal epilepsy formed disease modules. In summary, we show that in all common epilepsy types, 1.5-3% of patients carry epilepsy-associated CNVs. The characteristics of risk CNVs vary tremendously across and within epilepsy types. Thus, we advocate genome-wide genomic testing to identify all disease-associated types of CNVs.
Keywords: DNA Copy Number Variations; Epilepsy; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male

Estimation of the carrier frequency of fumarate hydratase alterations and implications for kidney cancer risk in hereditary leiomyomatosis and renal cancer. - Shuch, Brian; Li, Shantao; Risch, Harvey; Bindra, Ranjit S; McGillivray, Patrick D; Gerstein, Mark (Cancer, 2020)
BACKGROUND: Hereditary leiomyomatosis and renal cancer (HLRCC) is a cancer syndrome associated with a germline mutation in fumarate hydratase (FH). The syndrome is associated with cutaneous and uterine leiomyomas, and some patients develop a lethal form of kidney cancer. This study provides estimates for the FH carrier frequency and kidney cancer penetrance. METHODS: Data sets containing sequencing data for the FH gene were used: the 1000 Genomes Project (1000GP) and the Exome Aggregation Consortium (ExAC). Alterations in the FH gene were characterized on the basis of different variant risk tiers: 1) ClinVar annotated variants, 2) loss-of-function alterations, and 3) highly impactful missense alterations. The cumulative incidence of FH alterations overall and by different world populations was evaluated in 1000GP and ExAC. A lifetime penetrance of HLRCC kidney cancer risk was generated with 3 estimates of the annual incidence. RESULTS: The overall allele frequencies of tier 1 to 3 FH alterations in the ExAC and 1000GP data sets were 2.54 × 10 (1 in 393) and 1.20 × 10 (1 in 835), respectively. There were differences in the allele frequencies of FH alterations between world populations. Based on various estimates of the percentage of kidney cancers with FH alterations, the lifetime kidney cancer penetrance for carrier estimate 3 in ExAC was 1.7% to 5.8%. CONCLUSIONS: FH alterations are common and are carried by approximately 1 in 1000 individuals according to the more conservative estimates. The lifetime kidney cancer penetrance appears lower than previously estimated. Although databases are not population cohorts, they provide a useful quantitative estimate of rare variants with low penetrance.
Keywords: Adult; Exome; Female; Fumarate Hydratase; Gene Frequency; Genetic Predisposition to Disease; Germ-Line Mutation; Heterozygote; Humans; Kidney; Kidney Neoplasms; Leiomyomatosis; Male; Middle Aged; Neoplastic Syndromes, Hereditary; Risk Factors; Skin Neoplasms; Uterine Neoplasms

Evaluating systematic reanalysis of clinical genomic data in rare disease from single center experience and literature review. - Tan, Natalie B; Stapleton, Rachel; Stark, Zornitza; Delatycki, Martin B; Yeung, Alison; Hunter, Matthew F; Amor, David J; Brown, Natasha J; Stutterd, Chloe A; McGillivray, George; Yap, Patrick; Regan, Matthew; et al. (Mol Genet Genomic Med, 2020)
BACKGROUND: Our primary aim was to evaluate the systematic reanalysis of singleton exome sequencing (ES) data for unsolved cases referred for any indication. A secondary objective was to undertake a literature review of studies examining the reanalysis of genomic data from unsolved cases. METHODS: We examined data from 58 unsolved cases referred between June 2016 and March 2017. First reanalysis at 4-13 months after the initial report considered genes newly associated with disease since the original analysis; second reanalysis at 9-18 months considered all disease-associated genes. At 25-34 months we reviewed all cases and the strategies which solved them. RESULTS: Reanalysis of existing ES data alone at two timepoints did not yield new diagnoses. Over the same timeframe, 10 new diagnoses were obtained (17%) from additional strategies, such as microarray detection of copy number variation, repeat sequencing to improve coverage, and trio sequencing. Twenty-seven peer-reviewed articles were identified on the literature review, with a median new diagnosis rate via reanalysis of 15% and median reanalysis timeframe of 22 months. CONCLUSION: Our findings suggest that an interval of greater than 18 months from the original report may be optimal for reanalysis. We also recommend a multi-faceted strategy for cases remaining unsolved after singleton ES.

Evaluation of the VISAGE Basic Tool for Appearance and Ancestry Prediction Using PowerSeq Chemistry on the MiSeq FGx System. - Palencia-Madrid, Leire; Xavier, Catarina; de la Puente, Maria; Hohoff, Carsten; Phillips, Christopher; Kayser, Manfred; Parson, Walther (Genes (Basel), 2020)
The study of DNA to predict externally visible characteristics (EVCs) and the biogeographical ancestry (BGA) from unknown samples is gaining relevance in forensic genetics. Technical developments in Massively Parallel Sequencing (MPS) enable the simultaneous analysis of hundreds of DNA markers, which improves successful Forensic DNA Phenotyping (FDP). The EU-funded VISAGE (VISible Attributes through GEnomics) Consortium has developed various targeted MPS-based lab tools to apply FDP in routine forensic analyses. Here, we present an evaluation of the VISAGE Basic tool for appearance and ancestry prediction based on PowerSeq chemistry (Promega) on a MiSeq FGx System (Illumina). The panel consists of 153 single nucleotide polymorphisms (SNPs) that provide information about EVCs (41 SNPs for eye, hair and skin color from HIrisPlex-S) and continental BGA (115 SNPs; three overlap with the EVCs SNP set). The assay was evaluated for sensitivity, repeatability and genotyping concordance, as well as its performance with casework-type samples. This targeted MPS assay provided complete genotypes at all 153 SNPs down to 125 pg of input DNA and 99.67% correct genotypes at 50 pg. It was robust in terms of repeatability and concordance and provided useful results with casework-type samples. The results suggest that this MPS assay is a useful tool for basic appearance and ancestry prediction in forensic genetics for users interested in applying PowerSeq chemistry and MiSeq for this purpose.
Keywords: DNA Fingerprinting; Eye Color; Forensic Genetics; Genetic Markers; Genotype; Hair Color; High-Throughput Nucleotide Sequencing; Humans; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Skin Pigmentation; Software

Exome sequencing implicates genetic disruption of prenatal neuro-gliogenesis in sporadic congenital hydrocephalus. - Jin, Sheng Chih; Dong, Weilai; Kundishora, Adam J; Panchagnula, Shreyas; Moreno-De-Luca, Andres; Furey, Charuta G; Allocco, August A; Walker, Rebecca L; Nelson-Williams, Carol; Smith, Hannah; Dunbar, Ashley; Conine, Sierra; et al. (Nat Med, 2020)
Congenital hydrocephalus (CH), characterized by enlarged brain ventricles, is considered a disease of excessive cerebrospinal fluid (CSF) accumulation and thereby treated with neurosurgical CSF diversion with high morbidity and failure rates. The poor neurodevelopmental outcomes and persistence of ventriculomegaly in some post-surgical patients highlight our limited knowledge of disease mechanisms. Through whole-exome sequencing of 381 patients (232 trios) with sporadic, neurosurgically treated CH, we found that damaging de novo mutations account for >17% of cases, with five different genes exhibiting a significant de novo mutation burden. In all, rare, damaging mutations with large effect contributed to ~22% of sporadic CH cases. Multiple CH genes are key regulators of neural stem cell biology and converge in human transcriptional networks and cell types pertinent for fetal neuro-gliogenesis. These data implicate genetic disruption of early brain development, not impaired CSF dynamics, as the primary pathomechanism of a significant number of patients with sporadic CH.
Keywords: Brain; Cerebral Ventricles; Exome; Female; Genetic Predisposition to Disease; Humans; Hydrocephalus; Male; Mutation; Neural Stem Cells; Neurogenesis; Neuroglia; Transcription Factors; Tripartite Motif Proteins; Ubiquitin-Protein Ligases; Whole Exome Sequencing

Exome Sequencing Implicates Impaired GABA Signaling and Neuronal Ion Transport in Trigeminal Neuralgia. - Dong, Weilai; Jin, Sheng Chih; Allocco, August; Zeng, Xue; Sheth, Amar H; Panchagnula, Shreyas; Castonguay, Annie; Lorenzo, Louis-Étienne; Islam, Barira; Brindle, Geneviève; Bachand, Karine; Hu, Jamie; et al. (iScience, 2020)
Trigeminal neuralgia (TN) is a common, debilitating neuropathic face pain syndrome often resistant to therapy. The familial clustering of TN cases suggests that genetic factors play a role in disease pathogenesis. However, no unbiased, large-scale genomic study of TN has been performed to date. Analysis of 290 whole exome-sequenced TN probands, including 20 multiplex kindreds and 70 parent-offspring trios, revealed enrichment of rare, damaging variants in GABA receptor-binding genes in cases. Mice engineered with a TN-associated mutation (p.Cys188Trp) in the GABA receptor Cl channel γ-1 subunit () exhibited trigeminal mechanical allodynia and face pain behavior. Other TN probands harbored rare damaging variants in Na and Ca channels, including a significant variant burden in the α-1H subunit of the voltage-gated Ca channel Ca3.2 (). These results provide exome-level insight into TN and implicate genetically encoded impairment of GABA signaling and neuronal ion transport in TN pathogenesis.

Exome sequencing in patients with microphthalmia, anophthalmia, and coloboma (MAC) from a consanguineous population. - Islam, Farrah; Htun, Stephanie; Lai, Li-Wen; Krall, Max; Poranki, Menitha; Martin, Pierre-Marie; Sobreira, Nara; Wohler, Elizabeth S; Yu, Jingwei; Moore, Anthony T; Slavotinek, Anne M (Clin Genet, 2020)
Next-generation sequencing strategies have resulted in mutation detection rates of 21% to 61% in small cohorts of patients with microphthalmia, anophthalmia and coloboma (MAC), but despite progress in identifying novel causative genes, many patients remain without a genetic diagnosis. We studied a cohort of 19 patients with MAC who were ascertained from a population with high rates of consanguinity. Using single nucleotide polymorphism (SNP) arrays and whole exome sequencing (WES), we identified one pathogenic variant in TENM3 in a patient with cataracts in addition to MAC. We also detected novel variants of unknown significance in genes that have previously been associated with MAC, including KIF26B, MICU1 and CDON, and identified variants in candidate genes for MAC from the Wnt signaling pathway, comprising LRP6, WNT2B and IQGAP1, but our findings do not prove causality. Plausible variants were not found for many of the cases, indicating that our current understanding of the pathogenesis of MAC, a highly heterogeneous group of ocular defects, remains incomplete.

Exome sequencing reveals a novel variant in causing intracranial aneurysm in a Chinese family. - Ding, Xinghuan; Zhao, Sen; Zhang, Qianqian; Yan, Zihui; Wang, Yang; Wu, Yong; Li, Xiaoxin; Liu, Jian; Niu, Yuchen; Zhang, Yisen; Zhang, Mingqi; Wang, Huizi; et al. (J Neurointerv Surg, 2020)
BACKGROUND: Genetic risk factors play an important role in the pathogenesis of familial intracranial aneurysms (FIAs); however, the molecular mechanisms remain largely unknown. OBJECTIVE: To investigate potential FIA-causing genetic variants by rare variant interrogation and a family-based genomics approach in a large family with an extensive multigenerational pedigree with FIAs. METHOD: Exome sequencing (ES) was performed in a dominant likely family with intracranial aneurysms (IAs). Variants were analyzed by an in-house developed pipeline and prioritized using various filtering strategies, including population frequency, variant type, and predicted variant pathogenicity. Sanger sequencing was also performed to evaluate the segregation of the variants with the phenotype. RESULTS: Based on the ES data obtained from five individuals from a family with 7/21 living members affected with IAs, a total of 14 variants were prioritized as candidate variants. Familial segregation analysis revealed that c.2519T>C (p.Leu840Pro) segregated in accordance with Mendelian expectations with the phenotype within the family-that is, present in all IA-affected cases and absent from all unaffected members of the second generation. This missense variant is absent from public databases (1000genome, ExAC, gnomAD, ESP5400), and has damaging predictions by bioinformatics tools (Gerp ++ score = 5.88, CADD score = 16.43, MutationTaster score = 1, LRT score = 0). In addition, 840Leu in NFX1 is robustly conserved in mammals and maps in a region before the RING-type zinc finger domain. CONCLUSION: c.2519T>C (p.Leu840Pro) may contribute to the pathogenetics of a subset of FIAs.
Keywords: Adult; Asian Continental Ancestry Group; Computational Biology; Exome; Female; Genetic Variation; Humans; Intracranial Aneurysm; Male; Middle Aged; Pedigree; Phenotype; Repressor Proteins

Expanding the clinical and molecular spectrum of ATP6V1A related metabolic cutis laxa. - Vogt, Guido; El Choubassi, Naji; Herczegfalvi, Ágnes; Kölbel, Heike; Lekaj, Anja; Schara, Ulrike; Holtgrewe, Manuel; Krause, Sabine; Horvath, Rita; Schuelke, Markus; Hübner, Christoph; Mundlos, Stefan; et al. (J Inherit Metab Dis, 2020)
Several inborn errors of metabolism show cutis laxa as a highly recognizable feature. One group of these metabolic cutis laxa conditions is autosomal recessive cutis laxa type 2 caused by defects in v-ATPase components or the mitochondrial proline cycle. Besides cutis laxa, muscular hypotonia and cardiac abnormalities are hallmarks of autosomal recessive cutis laxa type 2D (ARCL2D) due to pathogenic variants in ATP6V1A encoding subunit A of the v-ATPase. Here, we report on three affected individuals from two families with ARCL2D in whom we performed whole exome and Sanger sequencing. We performed functional studies in fibroblasts from one individual, summarized all known probands' clinical, molecular, and biochemical features and compared them, also to other metabolic forms of cutis laxa. We identified novel missense and the first nonsense variant strongly affecting ATP6V1A expression. All six ARCL2D affected individuals show equally severe cutis laxa and dysmorphism at birth. While for one no information was available, two died in infancy and three are now adolescents with mild or absent intellectual disability. Muscular weakness, ptosis, contractures, and elevated muscle enzymes indicated a persistent myopathy. In cellular studies, a fragmented Golgi compartment, a delayed Brefeldin A-induced retrograde transport and glycosylation abnormalities were present in fibroblasts from two individuals. This is the second and confirmatory report on pathogenic variants in ATP6V1A as the cause of this extremely rare condition and the first to describe a nonsense allele. Our data highlight the tremendous clinical variability of ATP6V1A related phenotypes even within the same family.

Expanding the disease phenotype of ADSSL1-associated myopathy in non-Korean patients. - Mroczek, Magdalena; Durmus, Hacer; Bijarnia-MAHy, Sunita; Topf, Ana; Ghaoui, Roula; Bryen, Samantha; Duff, Jennifer; England, Eleina; Cooper, Sandra T; MacArthur, Daniel G; Straub, Volker (Neuromuscul Disord, 2020)
Adenylosuccinate synthase (ADSSL1) is a muscle specific enzyme involved in the purine nucleotide cycle and responsible for the conversion of inosine monophosphate to adenosine monophosphate. Since 2016, when mutations in the ADSSL1 gene were first described to be associated with an adult onset distal myopathy, nine patients with compound heterozygous variants in the ADSSL1 gene, all of Korean origin, have been identified. Here we report a novel ADSSL1 mutation and describe two sporadic cases of Turkish and Indian origin. Many of the clinical features of both patients and muscle histopathology and muscle MRI findings, were in accordance with previously reported findings in the adult onset distal myopathy individuals. However, one of our patients presented with progressive, proximally pronounced weakness, severe muscle atrophy and early contractures. Thus, mutations in ADSSL1 have to be considered in patients with both distal and proximal muscle weakness and across various ethnicities.

Expanding the phenotypic spectrum in RDH12-associated retinal disease. - Scott, Hilary A; Place, Emily M; Ferenchak, Kevin; Zampaglione, Erin; Wagner, Naomi E; Chao, Katherine R; DiTroia, Stephanie P; Navarro-Gomez, Daniel; Mukai, Shizuo; Huckfeldt, Rachel M; Pierce, Eric A; Bujakowska, Kinga M (Cold Spring Harb Mol Case Stud, 2020)
Retinol dehydrogenase 12, RDH12, plays a pivotal role in the visual cycle to ensure the maintenance of normal vision. Alterations in activity of this protein result in photoreceptor death and decreased vision beginning at an early age and progressing to substantial vision loss later in life. Here we describe 11 patients with retinal degeneration that underwent next-generation sequencing (NGS) with a targeted panel of all currently known inherited retinal degeneration (IRD) genes and whole-exome sequencing to identify the genetic causality of their retinal disease. These patients display a range of phenotypic severity prompting clinical diagnoses of macular dystrophy, cone-rod dystrophy, retinitis pigmentosa, and early-onset severe retinal dystrophy all attributed to biallelic recessive mutations in We report 15 causal alleles and expand the repertoire of known mutations with four novel variants: c.215A > G (p.Asp72Gly); c.362T > C (p.Ile121Thr); c.440A > C (p.Asn147Thr); and c.697G > A (p.Val233Ille). The broad phenotypic spectrum observed with biallelic mutations has been observed in other genetic forms of IRDs, but the diversity is particularly notable here given the prior association of primarily with severe early-onset disease. This breadth emphasizes the importance of broad genetic testing for inherited retinal disorders and extends the pool of individuals who may benefit from imminent gene-targeted therapies.
Keywords: Adolescent; Adult; Alcohol Oxidoreductases; Alleles; Amino Acid Substitution; Child; Child, Preschool; Female; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Humans; Male; Mutation; Optical Imaging; Pedigree; Phenotype; Retinal Diseases; Tomography, Optical Coherence; Whole Exome Sequencing; Young Adult

Extremity anomalies associated with Robinow syndrome. - Abu-Ghname, Amjed; Trost, Jeffrey; Davis, Matthew J; Sutton, V Reid; Zhang, Chaofan; Guillen, Diana E; Carvalho, Claudia M B; Maricevich, Renata S (Am J Med Genet A, 2020)
Robinow syndrome, a rare genetic disorder, is characterized by skeletal dysplasia with, among other anomalies, extremity and hand anomalies. There is locus heterogeneity and both dominant and recessive inheritance. A detailed description of associated extremity and hand anomalies does not currently exist due to the rarity of this syndrome. This study seeks to document the hand anomalies present in Robinow syndrome to allow for improved rates of timely and accurate diagnosis. A focused assessment of the extremities and stature was performed using clinical examination and standard photographic images. A total of 13 patients with clinical and molecular diagnosis consistent with dominant Robinow syndrome or recessive Robinow syndrome were evaluated. All patients had limb shortening, the most common of which was mesomelia; however, rhizomelia and micromelia were also seen. These findings are relevant to clinical characterization, particularly as Robinow syndrome has classically been defined as a "mesomelic disorder." A total of eight distinct hand anomalies were identified in 12 patients with both autosomal recessive and dominant forms of Robinow syndrome. One patient did not present with any hand differences. The most common hand findings included brachydactyly, broad thumbs, and clinodactyly. A thorough understanding of the breadth of Robinow syndrome-associated extremity and hand anomalies can aid in early patient identification, improving rates of timely diagnosis and allowing for proactive management of sequelae.

Forensic evaluation of the Asia Pacific ancestry-informative MAPlex assay. - Xavier, C; de la Puente, M; Phillips, C; Eduardoff, M; Heidegger, A; Mosquera-Miguel, A; Freire-Aradas, A; Lagace, R; Wootton, S; Power, D; Parson, W; Lareu, M V; et al. (Forensic Sci Int Genet, 2020)
DNA intelligence, and particularly the inference of biogeographical ancestry (BGA) is increasing in interest, and relevance within the forensic genetics community. The majority of current MPS-based forensic ancestry-informative assays focus on the differentiation of major global populations. The recently published MAPlex (Multiplex for the Asia Pacific) panel contains 144 SNPs and 20 microhaplotypes and aims to improve the differentiation of populations in the Asia Pacific region. This study reports the first forensic evaluation of the MAPlex panel using AmpliSeq technology and Ion S5 sequencing. This study reports on the overall performance of MAPlex including the assay's sequence coverage distribution and stability, baseline noise and description of problematic SNPs. Dilution series, artificially degraded and mixed DNA samples were also analysed to evaluate the sensitivity of the panel with challenging or compromised forensic samples. As the first panel to combine biallelic SNPs, multiple-allele SNPs and microhaplotypes, the MAPlex assay demonstrated an enhanced capacity for mixture detection, not easily performed with common binary SNPs. This performance evaluation indicates that MAPlex is a robust, stable and highly sensitive assay that is applicable to forensic casework for the prediction of BGA.

Four Individuals with a Homozygous Mutation in Exon 1f of the Gene and Associated Myasthenic Features. - Mroczek, Magdalena; Durmus, Hacer; Topf, Ana; Parman, Yesim; Straub, Volker (Genes (Basel), 2020)
We identified the known c.1_9del mutation in the gene in four unrelated females from consanguineous families of Turkish origin. All individuals presented with slowly progressive limb-girdle weakness without any dermatological findings, and dystrophic changes observed in their muscle biopsies. Additionally, the neurological examination revealed ptosis, facial weakness, fatigability, and muscle cramps in all four cases. In two patients, repetitive nerve stimulation showed a borderline decrement and a high jitter was detected in all patients by single-fiber electromyography. Clinical improvement was observed after treatment with pyridostigmine and salbutamol was started. We further characterize the phenotype of patients with limb-girdle muscular dystrophy R17 clinically, by muscle magnetic resonance imaging (MRI) features and by describing a common 3.8 Mb haplotype in three individuals from the same geographical region. In addition, we review the neuromuscular symptoms associated with mutations and the role of plectin in the neuromuscular junction.
Keywords: Adolescent; Adult; Child; Exons; Female; Homozygote; Humans; Muscular Dystrophies, Limb-Girdle; Mutation; Myasthenic Syndromes, Congenital; Phenotype; Plectin

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide. - Gonzaga-Jauregui, Claudia; Yesil, Gözde; Nistala, Harikiran; Gezdirici, Alper; Bayram, Yavuz; Nannuru, Kalyan C; Pehlivan, Davut; Yuan, Bo; Jimenez, Johanna; Sahin, Yavuz; Paine, Ingrid S; Akdemir, Zeynep Coban; et al. (Eur J Hum Genet, 2020)
Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto Rican descent with multiple affected adult individuals. We modeled the orthologous variant in murine Col27a1 and found it recapitulates some of the major Steel syndrome associated skeletal features including reduced body length, scoliosis, and a more rounded skull shape. Characterization of the in vivo murine model shows abnormal collagen deposition in the extracellular matrix and disorganization of the proliferative zone of the growth plate. We report additional COL27A1 pathogenic variant alleles identified in unrelated consanguineous Turkish kindreds suggesting Clan Genomics and identity-by-descent homozygosity contributing to disease in this population. The hypothesis that carrier states for this autosomal recessive osteochondrodysplasia may contribute to common complex traits is further explored in a large clinical population cohort. Our findings augment our understanding of COL27A1 biology and its role in skeletal development; and expand the functional allelic architecture in this gene underlying both rare and common disease phenotypes.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Bone Development; Child; Child, Preschool; Consanguinity; Extracellular Matrix; Female; Fibrillar Collagens; Founder Effect; Gene Frequency; Hip Dislocation; Homozygote; Humans; Male; Mice; Mice, Inbred C57BL; Mutation; Pedigree; Scoliosis; Syndrome

Further delineation of the clinical spectrum of KAT6B disorders and allelic series of pathogenic variants. - Zhang, Li Xin; Lemire, Gabrielle; Gonzaga-Jauregui, Claudia; Molidperee, Sirinart; Galaz-Montoya, Carolina; Liu, David S; Verloes, Alain; Shillington, Amelle G; Izumi, Kosuke; Ritter, Alyssa L; Keena, Beth; Zackai, Elaine; et al. (Genet Med, 2020)
PURPOSE: Genitopatellar syndrome and Say-Barber-Biesecker-Young-Simpson syndrome are caused by variants in the KAT6B gene and are part of a broad clinical spectrum called KAT6B disorders, whose variable expressivity is increasingly being recognized. METHODS: We herein present the phenotypes of 32 previously unreported individuals with a molecularly confirmed diagnosis of a KAT6B disorder, report 24 new pathogenic KAT6B variants, and review phenotypic information available on all published individuals with this condition. We also suggest a classification of clinical subtypes within the KAT6B disorder spectrum. RESULTS: We demonstrate that cerebral anomalies, optic nerve hypoplasia, neurobehavioral difficulties, and distal limb anomalies other than long thumbs and great toes, such as polydactyly, are more frequently observed than initially reported. Intestinal malrotation and its serious consequences can be present in affected individuals. Additionally, we identified four children with Pierre Robin sequence, four individuals who had increased nuchal translucency/cystic hygroma prenatally, and two fetuses with severe renal anomalies leading to renal failure. We also report an individual in which a pathogenic variant was inherited from a mildly affected parent. CONCLUSION: Our work provides a comprehensive review and expansion of the genotypic and phenotypic spectrum of KAT6B disorders that will assist clinicians in the assessment, counseling, and management of affected individuals.
Keywords: Blepharophimosis; Exons; Histone Acetyltransferases; Humans; Intellectual Disability; Mutation

Gain-of-function variants identified in vigabatrin-hypersensitive epileptic encephalopathies. - Absalom, Nathan L; Liao, Vivian W Y; Kothur, Kavitha; Indurthi, Dinesh C; Bennetts, Bruce; Troedson, Christopher; Mohammad, Shekeeb S; Gupta, Sachin; McGregor, Iain S; Bowen, Michael T; Lederer, Damien; Mary, Sandrine; et al. (Brain Commun, 2020)
Variants in the gene encoding the β3-subunit of the γ-aminobutyric acid type A ( receptor are associated with various developmental and epileptic encephalopathies. Typically, these variants cause a loss-of-function molecular phenotype whereby γ-aminobutyric acid has reduced inhibitory effectiveness leading to seizures. Drugs that potentiate inhibitory GABAergic activity, such as nitrazepam, phenobarbital or vigabatrin, are expected to compensate for this and thereby reduce seizure frequency. However, vigabatrin, a drug that inhibits γ-aminobutyric acid transaminase to increase tonic γ-aminobutyric acid currents, has mixed success in treating seizures in patients with variants: some patients experience seizure cessation, but there is hypersensitivity in some patients associated with hypotonia, sedation and respiratory suppression. A variant that responds well to vigabatrin involves a truncation variant (p.Arg194*) resulting in a clear loss-of-function. We hypothesized that patients with a hypersensitive response to vigabatrin may exhibit a different γ-aminobutyric acid A receptor phenotype. To test this hypothesis, we evaluated the phenotype of variants in (p.Glu77Lys and p.Thr287Ile) associated with patients who are clinically hypersensitive to vigabatrin. We introduced the p.Glu77Lys and p.Thr287Ile variants into a concatenated synaptic and extrasynaptic γ-aminobutyric acid A receptor construct, to resemble the γ-aminobutyric acid A receptor expression by a patient heterozygous for the variant. The mRNA of these constructs was injected into oocytes and activation properties of each receptor measured by two-electrode voltage clamp electrophysiology. Results showed an atypical gain-of-function molecular phenotype in the p.Glu77Lys and p.Thr287Ile variants characterized by increased potency of γ-aminobutyric acid A without change to the estimated maximum open channel probability, deactivation kinetics or absolute currents. Modelling of the activation properties of the receptors indicated that either variant caused increased chloride flux in response to low concentrations of γ-aminobutyric acid that mediate tonic currents. We therefore propose that the hypersensitivity reaction to vigabatrin is a result of variants that exacerbate GABAergic tonic currents and caution is required when prescribing vigabatrin. In contrast, drug strategies increasing tonic currents in loss-of-function variants are likely to be a safe and effective therapy. This study demonstrates that functional genomics can explain beneficial and adverse anti-epileptic drug effects, and propose that vigabatrin should be considered in patients with clear loss-of-function variants.

Gain-of-Function Variants in Dilated Cardiomyopathy. - Cowan, Jason R; Salyer, Lorien; Wright, Nathan T; Kinnamon, Daniel D; Amaya, Pedro; Jordan, Elizabeth; Bamshad, Michael J; Nickerson, Deborah A; Hershberger, Ray E (Circ Genom Precis Med, 2020)
BACKGROUND: Dilated cardiomyopathy (DCM) is a genetically heterogeneous cardiac disease characterized by progressive ventricular enlargement and reduced systolic function. Here, we report genetic and functional analyses implicating the rat sarcoma signaling protein, SOS1 (Son of sevenless homolog 1), in DCM pathogenesis. METHODS: Exome sequencing was performed on 412 probands and family members from our DCM cohort, identifying several variants with potential disease involvement. As several lines of evidence have implicated dysregulated rat sarcoma signaling in the pathogenesis of DCM, we assessed functional impact of each variant on the activation of ERK (extracellular signal-regulated kinase), AKT (protein kinase B), and JNK (c-Jun N-terminal kinase) pathways. Relative expression levels were determined by Western blot in HEK293T cells transfected with variant or wild-type human expression constructs. RESULTS: A rare variant [c.571G>A, p.(Glu191Lys)] was found to segregate alongside an A-band truncating variant in a pedigree with aggressive, early-onset DCM. Reduced disease severity in the absence of the variant suggested its potential involvement as a genetic risk factor for DCM in this family. Exome sequencing identified 5 additional variants with potential disease involvement in 4 other families [c.1820T>C, p.(Ile607Thr); c.2156G>C, p.(Gly719Ala); c.2230A>G, p.(Arg744Gly); c.2728G>C, p.(Asp910His); c.3601C>T, p.(Arg1201Trp)]. Impacted amino acids occupied a number of functional domains relevant to SOS1 activity, including the N-terminal histone fold, as well as the C-terminal REM (rat sarcoma exchange motif), CDC25 (cell division cycle 25), and PR (proline-rich) tail domains. Increased phosphorylated ERK expression relative to wild-type levels was seen for all 6 variants, paralleling known disease-relevant signaling profiles. CONCLUSIONS: These data support gain-of-function variation in as a contributing factor to isolated DCM.

Gene-based analyses of the maternal genome implicate maternal effect genes as risk factors for conotruncal heart defects. - Sewda, Anshuman; Agopian, A J; Goldmuntz, Elizabeth; Hakonarson, Hakon; Morrow, Bernice E; Musfee, Fadi; Taylor, Deanne; Mitchell, Laura E (PLoS One, 2020)
Congenital heart defects (CHDs) affect approximately 1% of newborns. Epidemiological studies have identified several genetically-mediated maternal phenotypes (e.g., pregestational diabetes, chronic hypertension) that are associated with the risk of CHDs in offspring. However, the role of the maternal genome in determining CHD risk has not been defined. We present findings from gene-level, genome-wide studies that link CHDs to maternal effect genes as well as to maternal genes related to hypertension and proteostasis. Maternal effect genes, which provide the mRNAs and proteins in the oocyte that guide early embryonic development before zygotic gene activation, have not previously been implicated in CHD risk. Our findings support a role for and suggest new pathways by which the maternal genome may contribute to the development of CHDs in offspring.
Keywords: Adult; Case-Control Studies; Child, Preschool; Family; Female; Genetic Testing; Heart Defects, Congenital; Humans; Hypertension; Infant; Infant, Newborn; Male; Maternal Exposure; Maternal Inheritance; Middle Aged; Oocytes; Pregnancy; Prenatal Exposure Delayed Effects; Proteostasis; Risk Factors

The genetic and clinical landscape of nanophthalmos and posterior microphthalmos in an Australian cohort. - Siggs, Owen M; Awadalla, Mona S; Souzeau, Emmanuelle; Staffieri, Sandra E; Kearns, Lisa S; Laurie, Kate; Kuot, AbrAHm; Qassim, Ayub; Edwards, Thomas L; Coote, Michael A; Mancel, Erica; Walland, Mark J; et al. (Clin Genet, 2020)
Nanophthalmos and posterior microphthalmos are ocular abnormalities in which both eyes are abnormally small, and typically associated with extreme hyperopia. We recruited 40 individuals from 13 kindreds with nanophthalmos or posterior microphthalmos, with 12 probands subjected to exome sequencing. Nine probands (69.2%) were assigned a genetic diagnosis, with variants in MYRF, TMEM98, MFRP, and PRSS56. Two of four PRSS56 families harbored the previously described c.1066dupC variant implicated in over half of all reported PRSS56 kindreds, with different surrounding haplotypes in each family suggesting a mutational hotspot. Individuals with a genetic diagnosis had shorter mean axial lengths and higher hyperopia than those without, with recessive forms associated with the most extreme phenotypes. These findings detail the genetic architecture of nanophthalmos and posterior microphthalmos in a cohort of predominantly European ancestry, their relative clinical phenotypes, and highlight the shared genetic architecture of rare and common disorders of refractive error.

Genetic and molecular mechanism for distinct clinical phenotypes conveyed by allelic truncating mutations implicated in FBN1. - Lin, Mao; Liu, Zhenlei; Liu, Gang; Zhao, Sen; Li, Chao; Chen, Weisheng; Coban Akdemir, Zeynep; Lin, Jiachen; Song, Xiaofei; Wang, Shengru; Xu, Qiming; Zhao, Yanxue; et al. (Mol Genet Genomic Med, 2020)
BACKGROUND: The molecular and genetic mechanisms by which different single nucleotide variant alleles in specific genes, or at the same genetic locus, cause distinct disease phenotypes often remain unclear. Allelic truncating mutations of FBN1 could cause either classical Marfan syndrome (MFS) or a more complicated phenotype associated with Marfanoid-progeroid-lipodystrophy syndrome (MPLS). METHODS: We investigated a small cohort, encompassing two classical MFS and one MPLS subjects from China, whose clinical presentation included scoliosis potentially requiring surgical intervention. Targeted next generation sequencing was performed on all the participants. We analyzed the molecular diagnosis, clinical features, and the potential molecular mechanism involved in the MPLS subject in our cohort. RESULTS: We report a novel de novo FBN1 mutation for the first Chinese subject with MPLS, a more complicated fibrillinopathy, and two subjects with more classical MFS. We further predict that the MPLS truncating mutation, and others previously reported, is prone to escape the nonsense-mediated decay (NMD), while MFS mutations are predicted to be subjected to NMD. Also, the MPLS mutation occurs within the glucogenic hormone asprosin domain of FBN1. In vitro experiments showed that the single MPLS mutation p.Glu2759Cysfs*9 appears to perturb proper FBN1 protein aggregation as compared with the classical MFS mutation p.Tyr2596Thrfs*86. Both mutations appear to upregulate SMAD2 phosphorylation in vitro. CONCLUSION: We provide direct evidence that a dominant-negative interaction of FBN1 potentially explains the complex MPLS phenotypes through genetic and functional analysis. Our study expands the mutation spectrum of FBN1 and highlights the potential molecular mechanism for MPLS.
Keywords: Adolescent; Adult; Child; Female; Fibrillin-1; HEK293 Cells; Humans; Lipodystrophy; Marfan Syndrome; Mutation; Phenotype; Progeria; Protein Domains; Smad2 Protein

Genetic Burden Contributing to Extremely Low or High Bone Mineral Density in a Senior Male Population From the Osteoporotic Fractures in Men Study (MrOS). - Chen, Shan; Jain, Mahim; Jhangiani, Shalini; Akdemir, Zeynep C; Campeau, Philippe M; Klein, Robert F; Nielson, Carrie; Dai, Hongzheng; Muzny, Donna M; Boerwinkle, Eric; Gibbs, Richard A; Orwoll, Eric S; et al. (JBMR Plus, 2020)
Worldwide, one in five men aged over 50 years will experience osteoporosis or a clinical bone fracture, with a greater fracture-related mortality rate than women. However, the genetic etiology of osteoporosis in men is still poorly understood. We aimed to identify the genetic variants and candidate genes associated with extremely low or high BMD for a better understanding of the biology underlying low bone density that may point to potential therapeutic targets for increasing bone mass. Subjects from the Osteoporotic Fractures in Men Study (MrOS) cohort were evaluated by age and BMI-adjusted total hip BMD. Those with BMD values 3 SDs away from the mean were selected and the remaining individuals whose adjusted BMD ranked at the highest or lowest 100 were included. Men with the lowest adjusted BMD ( = 98) and highest adjusted BMD ( = 110) were chosen for exome sequencing. Controls ( = 82) were men of Northern and Western European descent from the US Utah population of the 1000 Genomes Project. Fisher's exact test was performed to compare low- or high-BMD subjects with controls for single-gene associations. Additionally, sets of candidate genes causative of heritable disorders of connective tissue, including osteogenesis imperfecta (OI) and Ehlers-Danlos syndrome (EDS), were grouped for multigene and mutation burden analyses. No single-gene associations with rare variants were found for either the low BMD group (33 genes) or high BMD group (18 genes). In the group of OI genes, we detected a significant threefold increased accumulation of rare variants in low-BMD subjects compared with controls ( = 0.009). Additionally, genes associated with EDS had a twofold increased frequency in low-BMD subjects compared with controls ( = 0.03). These findings reveal a rare variant burden in OI and EDS disease genes at low BMD, which suggests a potential gene-panel approach to screen for multivariant associations in larger cohorts. © 2019 The Authors. published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.

The Genetic Control of Stoichiometry Underlying Autism. - Darnell, Robert B (Annu Rev Neurosci, 2020)
Autism is a common and complex neurologic disorder whose scientific underpinnings have begun to be established in the past decade. The essence of this breakthrough has been a focus on families, where genetic analyses are strongest, versus large-scale, case-control studies. Autism genetics has progressed in parallel with technology, from analyses of copy number variation to whole-exome sequencing (WES) and whole-genome sequencing (WGS). Gene mutations causing complete loss of function account for perhaps one-third of cases, largely detected through WES. This limitation has increased interest in understanding the regulatory variants of genes that contribute in more subtle ways to the disorder. Strategies combining biochemical analysis of gene regulation, WGS analysis of the noncoding genome, and machine learning have begun to succeed. The emerging picture is that careful control of the amounts of transcription, mRNA, and proteins made by key brain genes-stoichiometry-plays a critical role in defining the clinical features of autism.

Genetic diagnoses in epilepsy: The impact of dynamic exome analysis in a pediatric cohort. - Rochtus, Anne; Olson, Heather E; Smith, Lacey; Keith, Louisa G; El Achkar, Christelle; Taylor, Alan; Mahida, Sonal; Park, Meredith; Kelly, McKenna; Shain, Catherine; Rockowitz, Shira; Rosen Sheidley, Beth; et al. (Epilepsia, 2020)
OBJECTIVE: We evaluated the yield of systematic analysis and/or reanalysis of whole exome sequencing (WES) data from a cohort of well-phenotyped pediatric patients with epilepsy and suspected but previously undetermined genetic etiology. METHODS: We identified and phenotyped 125 participants with pediatric epilepsy. Etiology was unexplained at the time of enrollment despite clinical testing, which included chromosomal microarray (57 patients), epilepsy gene panel (n = 48), both (n = 28), or WES (n = 8). Clinical epilepsy diagnoses included developmental and epileptic encephalopathy (DEE), febrile infection-related epilepsy syndrome, Rasmussen encephalitis, and other focal and generalized epilepsies. We analyzed WES data and compared the yield in participants with and without prior clinical genetic testing. RESULTS: Overall, we identified pathogenic or likely pathogenic variants in 40% (50/125) of our study participants. Nine patients with DEE had genetic variants in recently published genes that had not been recognized as epilepsy-related at the time of clinical testing (FGF12, GABBR1, GABBR2, ITPA, KAT6A, PTPN23, RHOBTB2, SATB2), and eight patients had genetic variants in candidate epilepsy genes (CAMTA1, FAT3, GABRA6, HUWE1, PTCHD1). Ninety participants had concomitant or subsequent clinical genetic testing, which was ultimately explanatory for 26% (23/90). Of the 67 participants whose molecular diagnoses were "unsolved" through clinical genetic testing, we identified pathogenic or likely pathogenic variants in 17 (25%). SIGNIFICANCE: Our data argue for early consideration of WES with iterative reanalysis for patients with epilepsy, particularly those with DEE or epilepsy with intellectual disability. Rigorous analysis of WES data of well-phenotyped patients with epilepsy leads to a broader understanding of gene-specific phenotypic spectra as well as candidate disease gene identification. We illustrate the dynamic nature of genetic diagnosis over time, with analysis and in some cases reanalysis of exome data leading to the identification of disease-associated variants among participants with previously nondiagnostic results from a variety of clinical testing strategies.
Keywords: Adolescent; Adult; Age of Onset; Brain Diseases; Child; Child, Preschool; Chromosomes, Human; Cohort Studies; Epilepsy; Epilepsy, Generalized; Exome; Female; Genetic Testing; Genetic Variation; Humans; Infant; Male; Microarray Analysis; Phenotype; Whole Exome Sequencing; Young Adult

Genetic diagnosis in the fetus. - Wojcik, Monica H; Reimers, Rebecca; Poorvu, Tabitha; Agrawal, Pankaj B (J Perinatol, 2020)
Many genetic disorders are detectable in the prenatal period, and the capacity to identify them has increased remarkably as molecular genetic testing techniques continue to improve and become incorporated into clinical practice. The indications for prenatal genetic testing vary widely, including follow-up of an anomaly found by routine ultrasound or maternal aneuploidy screening, a family history of genetic disease, advanced maternal or paternal age, or evaluation of a low-risk pregnancy due to parental concern. The interpretation of genetic variants identified in the prenatal period poses unique challenges due to the lack of ability for deep phenotyping as well as the option to make critical decisions regarding pregnancy continuation and perinatal management. In this review, we address the various modalities currently available and commonly used for genetic testing, including preimplantation genetic testing of embryos, cell-free DNA testing, and diagnostic procedures such as chorionic villous sampling, amniocentesis, or percutaneous umbilical blood sampling, from which samples may be sent for a wide variety of genetic tests. We discuss the difference between these modalities for the genetic diagnosis of a fetus, their strengths and weaknesses, and strategies for their optimal use in order to direct perinatal care.

Genetics of schizophrenia in the South African Xhosa. - Gulsuner, S; Stein, D J; Susser, E S; Sibeko, G; Pretorius, A; Walsh, T; Majara, L; Mndini, M M; Mqulwana, S G; Ntola, O A; Casadei, S; Ngqengelele, L L; et al. (Science, 2020)
Africa, the ancestral home of all modern humans, is the most informative continent for understanding the human genome and its contribution to complex disease. To better understand the genetics of schizophrenia, we studied the illness in the Xhosa population of South Africa, recruiting 909 cases and 917 age-, gender-, and residence-matched controls. Individuals with schizophrenia were significantly more likely than controls to harbor private, severely damaging mutations in genes that are critical to synaptic function, including neural circuitry mediated by the neurotransmitters glutamine, γ-aminobutyric acid, and dopamine. Schizophrenia is genetically highly heterogeneous, involving severe ultrarare mutations in genes that are critical to synaptic plasticity. The depth of genetic variation in Africa revealed this relationship with a moderate sample size and informed our understanding of the genetics of schizophrenia worldwide.
Keywords: Age Factors; Autistic Disorder; Bipolar Disorder; Dopamine; Female; gamma-Aminobutyric Acid; Genetic Variation; Glutamine; Humans; Male; Mutation; Neural Pathways; Schizophrenia; Sex Factors; South Africa; Synapses; Synaptic Transmission

Genome sequencing identifies a homozygous inversion disrupting QDPR as a cause for dihydropteridine reductase deficiency. - Lilleväli, Hardo; Pajusalu, Sander; Wojcik, Monica H; Goodrich, Julia; Collins, Ryan L; Murumets, Ülle; Tammur, Pille; Blau, Nenad; Lilleväli, Kersti; Õunap, Katrin (Mol Genet Genomic Med, 2020)
BACKGROUND: Dihydropteridine reductase (DHPR) is one of the key enzymes for maintaining in the organism the supply of tetrahydrobiopterin (BH ), an essential cofactor for aromatic amino acid hydroxylases. Its dysfunction causes the condition of hyperphenylalaninemia together with the lack of neurotransmitters. METHODS: We report a patient with biochemically diagnosed DHPR deficiency, with extensive molecular investigations undertaken to detect variations in quinoid dihydropteridine reductase (QDPR) gene. Sanger sequencing of QDPR coding regions, exome sequencing, QDPR mRNA PCR, and karyotyping were followed by trio genome sequencing. RESULTS: Short-read genome sequencing revealed a homozygous 9-Mb inversion disrupting QDPR. Structural variant breakpoints in chromosome 4 were located to intron 2 of QDPR at Chr4(GRCh38):g.17505522 and in intron 8 of the ACOX3 gene, Chr4(GRCh38):g.8398067). Both nonrelated parents carried the variant in heterozygous state. The inversion was not present in gnomAD structural variant database. CONCLUSION: Identification of the exact breakpoints now allows further straightforward molecular genetic testing of potential carriers of the inversion. This study extends the pathogenic variant spectrum of DHPR deficiency and highlights the role of structural variants in recessive metabolic disorders. To our knowledge, this is the first report on a large, canonical (rather than complex) homozygous pathogenic inversion detected by genome sequencing.
Keywords: Acyl-CoA Oxidase; Child; Chromosome Breakpoints; Chromosome Inversion; Chromosomes, Human, Pair 4; Female; Genetic Testing; Homozygote; Humans; Phenylketonurias; Whole Exome Sequencing

Genome-wide association meta-analysis for early age-related macular degeneration highlights novel loci and insights for advanced disease. - Winkler, Thomas W; Grassmann, Felix; Brandl, Caroline; Kiel, Christina; Günther, Felix; Strunz, Tobias; Weidner, Lorraine; Zimmermann, Martina E; Korb, Christina A; Poplawski, Alicia; Schuster, Alexander K; Müller-Nurasyid, Martina; et al. (BMC Med Genomics, 2020)
BACKGROUND: Advanced age-related macular degeneration (AMD) is a leading cause of blindness. While around half of the genetic contribution to advanced AMD has been uncovered, little is known about the genetic architecture of early AMD. METHODS: To identify genetic factors for early AMD, we conducted a genome-wide association study (GWAS) meta-analysis (14,034 cases, 91,214 controls, 11 sources of data including the International AMD Genomics Consortium, IAMDGC, and UK Biobank, UKBB). We ascertained early AMD via color fundus photographs by manual grading for 10 sources and via an automated machine learning approach for > 170,000 photographs from UKBB. We searched for early AMD loci via GWAS and via a candidate approach based on 14 previously suggested early AMD variants. RESULTS: Altogether, we identified 10 independent loci with statistical significance for early AMD: (i) 8 from our GWAS with genome-wide significance (P < 5 × 10), (ii) one previously suggested locus with experiment-wise significance (P < 0.05/14) in our non-overlapping data and with genome-wide significance when combining the reported and our non-overlapping data (together 17,539 cases, 105,395 controls), and (iii) one further previously suggested locus with experiment-wise significance in our non-overlapping data. Of these 10 identified loci, 8 were novel and 2 known for early AMD. Most of the 10 loci overlapped with known advanced AMD loci (near ARMS2/HTRA1, CFH, C2, C3, CETP, TNFRSF10A, VEGFA, APOE), except two that have not yet been identified with statistical significance for any AMD. Among the 17 genes within these two loci, in-silico functional annotation suggested CD46 and TYR as the most likely responsible genes. Presence or absence of an early AMD effect distinguished the known pathways of advanced AMD genetics (complement/lipid pathways versus extracellular matrix metabolism). CONCLUSIONS: Our GWAS on early AMD identified novel loci, highlighted shared and distinct genetics between early and advanced AMD and provides insights into AMD etiology. Our data provide a resource comparable in size to the existing IAMDGC data on advanced AMD genetics enabling a joint view. The biological relevance of this joint view is underscored by the ability of early AMD effects to differentiate the major pathways for advanced AMD.
Keywords: Case-Control Studies; Genetic Loci; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Macular Degeneration; Polymorphism, Single Nucleotide

A genome-wide case-only test for the detection of digenic inheritance in human exomes. - Kerner, Gaspard; Bouaziz, Matthieu; Cobat, Aurelie; Bigio, Benedetta; Timberlake, Andrew T; Bustamante, Jacinta; Lifton, Richard P; Casanova, Jean-Laurent; Abel, Laurent (Proc Natl Acad Sci U S A, 2020)
Whole-exome sequencing (WES) has facilitated the discovery of genetic lesions underlying monogenic disorders. Incomplete penetrance and variable expressivity suggest a contribution of additional genetic lesions to clinical manifestations and outcome. Some monogenic disorders may therefore actually be digenic. However, only a few digenic disorders have been reported, all discovered by candidate gene approaches applied to at least one locus. We propose here a two-locus genome-wide test for detecting digenic inheritance in WES data. This approach uses the gene as the unit of analysis and tests all pairs of genes to detect pairwise gene × gene interactions underlying disease. It is a case-only method, which has several advantages over classic case-control tests, in particular by avoiding recruitment of controls. Our simulation studies based on real WES data identified two major sources of type I error inflation in this case-only test: linkage disequilibrium and population stratification. Both were corrected by specific procedures. Moreover, our case-only approach is more powerful than the corresponding case-control test for detecting digenic interactions in various population stratification scenarios. Finally, we confirmed the potential of our unbiased, genome-wide approach by successfully identifying a previously reported digenic lesion in patients with craniosynostosis. Our case-only test is a powerful and timely tool for detecting digenic inheritance in WES data from patients.
Keywords: Craniosynostoses; Epistasis, Genetic; Exome; Genetic Linkage; Genetic Variation; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Models, Genetic; Multifactorial Inheritance; Whole Exome Sequencing

Genome-Wide Polygenic Score, Clinical Risk Factors, and Long-Term Trajectories of Coronary Artery Disease. - Hindy, George; Aragam, Krishna G; Ng, Kenney; Chaffin, Mark; Lotta, Luca A; Baras, Aris; Drake, Isabel; Orho-Melander, Marju; Melander, Olle; Kathiresan, Sekar; Khera, Amit V (Arterioscler Thromb Vasc Biol, 2020)
OBJECTIVE: To determine the relationship of a genome-wide polygenic score for coronary artery disease (GPS) with lifetime trajectories of CAD risk, directly compare its predictive capacity to traditional risk factors, and assess its interplay with the Pooled Cohort Equations (PCE) clinical risk estimator. Approach and Results: We studied GPS in 28 556 middle-aged participants of the Malmö Diet and Cancer Study, of whom 4122 (14.4%) developed CAD over a median follow-up of 21.3 years. A pronounced gradient in lifetime risk of CAD was observed-16% for those in the lowest GPS decile to 48% in the highest. We evaluated the discriminative capacity of the GPS-as assessed by change in the C-statistic from a baseline model including age and sex-among 5685 individuals with PCE risk estimates available. The increment for the GPS (+0.045, <0.001) was higher than for any of 11 traditional risk factors (range +0.007 to +0.032). Minimal correlation was observed between GPS and 10-year risk defined by the PCE (=0.03), and addition of GPS improved the C-statistic of the PCE model by 0.026. A significant gradient in lifetime risk was observed for the GPS, even among individuals within a given PCE clinical risk stratum. We replicated key findings-noting strikingly consistent results-in 325 003 participants of the UK Biobank. CONCLUSIONS: GPS-a risk estimator available from birth-stratifies individuals into varying trajectories of clinical risk for CAD. Implementation of GPS may enable identification of high-risk individuals early in life, decades in advance of manifest risk factors or disease.
Keywords: Adult; Aged; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Disease Risk Factors; Heredity; Humans; Incidence; Male; Middle Aged; Multifactorial Inheritance; Phenotype; Prognosis; Risk Assessment; Sweden; Time Factors; United Kingdom

Genotypic diversity and phenotypic spectrum of infantile liver failure syndrome type 1 due to variants in LARS1. - Lenz, Dominic; Smith, Desirée E C; Crushell, Ellen; Husain, Ralf A; Salomons, Gajja S; Alhaddad, Bader; Bernstein, Jonathan A; Bianzano, Alyssa; Biskup, Saskia; Brennenstuhl, Heiko; Caldari, Dominique; Dikow, Nicola; et al. (Genet Med, 2020)
PURPOSE: Biallelic variants in LARS1, coding for the cytosolic leucyl-tRNA synthetase, cause infantile liver failure syndrome 1 (ILFS1). Since its description in 2012, there has been no systematic analysis of the clinical spectrum and genetic findings. METHODS: Individuals with biallelic variants in LARS1 were included through an international, multicenter collaboration including novel and previously published patients. Clinical variables were analyzed and functional studies were performed in patient-derived fibroblasts. RESULTS: Twenty-five individuals from 15 families were ascertained including 12 novel patients with eight previously unreported variants. The most prominent clinical findings are recurrent elevation of liver transaminases up to liver failure and encephalopathic episodes, both triggered by febrile illness. Magnetic resonance image (MRI) changes during an encephalopathic episode can be consistent with metabolic stroke. Furthermore, growth retardation, microcytic anemia, neurodevelopmental delay, muscular hypotonia, and infection-related seizures are prevalent. Aminoacylation activity is significantly decreased in all patient cells studied upon temperature elevation in vitro. CONCLUSION: ILFS1 is characterized by recurrent elevation of liver transaminases up to liver failure in conjunction with abnormalities of growth, blood, nervous system, and musculature. Encephalopathic episodes with seizures can occur independently from liver crises and may present with metabolic stroke.
Keywords: Humans; Liver Failure; Muscle Hypotonia; Mutation; Seizures

Gomez-López-Hernández syndrome: A case report with clinical and molecular evaluation and literature review. - Perrone, Eduardo; D'Almeida, Vânia; de Macena Sobreira, Nara Lygia; de Mello, Claudia Berlim; de Oliveira, Allan Chiaratti; Burlin, Stênio; Soares, Maria de Fátima de Faria; Cernach, Mirlene Cecília Soares Pinho; Alvarez Perez, Ana Beatriz (Am J Med Genet A, 2020)
Gomez-López-Hernández syndrome (GLHS) is characterized by rhombencephalosynapsis (RES), alopecia, trigeminal anesthesia and a distinctive phenotype, including brachyturricephaly. It has been suggested that GLHS should be considered as part of the spectrum of RES-associated conditions that include alopecia, trigeminal anesthesia, and craniofacial anomalies, rather than a distinct entity. To the best of our knowledge, 57 patients with GLHS have been described. Despite its first description in 1979, the etiology of this syndrome remains unknown. Here, we describe, to our knowledge, the first case of a patient with GLHS who was molecularly evaluated and had been prenatally exposed to misoprostol. We also reviewed the clinical and morphological features of the patients described to date to better delineate the phenotype and focus on any evidence for adverse pregnancy outcomes or exposure, including teratogens.
Keywords: Abnormalities, Multiple; Alopecia; Cerebellum; Child; Child, Preschool; Craniofacial Abnormalities; Female; Growth Disorders; Humans; Magnetic Resonance Imaging; Misoprostol; Neurocutaneous Syndromes; Phenotype; Rhombencephalon; Trigeminal Nerve

The GTEx Consortium atlas of genetic regulatory effects across human tissues. (Science, 2020)
The Genotype-Tissue Expression (GTEx) project was established to characterize genetic effects on the transcriptome across human tissues and to link these regulatory mechanisms to trait and disease associations. Here, we present analyses of the version 8 data, examining 15,201 RNA-sequencing samples from 49 tissues of 838 postmortem donors. We comprehensively characterize genetic associations for gene expression and splicing in cis and trans, showing that regulatory associations are found for almost all genes, and describe the underlying molecular mechanisms and their contribution to allelic heterogeneity and pleiotropy of complex traits. Leveraging the large diversity of tissues, we provide insights into the tissue specificity of genetic effects and show that cell type composition is a key factor in understanding gene regulatory mechanisms in human tissues.
Keywords: Datasets as Topic; Disease; Female; Gene Expression Regulation; Genome-Wide Association Study; Humans; Male; Organ Specificity; Quantitative Trait Loci; Sequence Analysis, RNA

HEM1 deficiency disrupts mTORC2 and F-actin control in inherited immunodysregulatory disease. - Cook, Sarah A; Comrie, William A; Poli, M Cecilia; Similuk, Morgan; Oler, Andrew J; Faruqi, Aiman J; Kuhns, Douglas B; Yang, Sheng; Vargas-Hernandez, Alexander; Carisey, Alexandre F; Fournier, Benjamin; Anderson, D Eric; et al. (Science, 2020)
Immunodeficiency often coincides with hyperactive immune disorders such as autoimmunity, lymphoproliferation, or atopy, but this coincidence is rarely understood on a molecular level. We describe five patients from four families with immunodeficiency coupled with atopy, lymphoproliferation, and cytokine overproduction harboring mutations in , which encodes the hematopoietic-specific HEM1 protein. These mutations cause the loss of the HEM1 protein and the WAVE regulatory complex (WRC) or disrupt binding to the WRC regulator, Arf1, thereby impairing actin polymerization, synapse formation, and immune cell migration. Diminished cortical actin networks caused by WRC loss led to uncontrolled cytokine release and immune hyperresponsiveness. HEM1 loss also blocked mechanistic target of rapamycin complex 2 (mTORC2)-dependent AKT phosphorylation, T cell proliferation, and selected effector functions, leading to immunodeficiency. Thus, the evolutionarily conserved HEM1 protein simultaneously regulates filamentous actin (F-actin) and mTORC2 signaling to achieve equipoise in immune responses.
Keywords: Actins; ADP-Ribosylation Factor 1; CD4-Positive T-Lymphocytes; Cell Proliferation; Cytokines; Humans; Immunologic Deficiency Syndromes; Lymphoproliferative Disorders; Mechanistic Target of Rapamycin Complex 2; Membrane Proteins; Pedigree; Phosphorylation; Wiskott-Aldrich Syndrome Protein Family

Heme oxygenase-1 deficiency presenting with interstitial lung disease and hemophagocytic flares. - Chau, Alice S; Cole, Bonnie L; Debley, Jason S; Nanda, Kabita; Rosen, Aaron B I; Bamshad, Michael J; Nickerson, Deborah A; Torgerson, Troy R; Allenspach, Eric J (Pediatr Rheumatol Online J, 2020)
BACKGROUND: Heme oxygenase-1 (HMOX1) catalyzes the metabolism of heme into carbon monoxide, ferrous iron, and biliverdin. Through biliverdin reductase, biliverdin becomes bilirubin. HMOX1-deficiency is a rare autosomal recessive disorder with hallmark features of direct antibody negative hemolytic anemia with normal bilirubin, hyperinflammation and features similar to macrophage activation syndrome. Clinical findings have included asplenia, nephritis, hepatitis, and vasculitis. Pulmonary features and evaluation of the immune response have been limited. CASE PRESENTATION: We present a young boy who presented with chronic respiratory failure due to nonspecific interstitial pneumonia following a chronic history of infection-triggered recurrent hyperinflammatory flares. Episodes included hemolysis without hyperbilirubinemia, immunodeficiency, hepatomegaly with mild transaminitis, asplenia, leukocytosis, thrombocytosis, joint pain and features of macrophage activation with negative autoimmune serologies. Lung biopsy revealed cholesterol granulomas. He was found post-mortem by whole exome sequencing to have a compound heterozygous paternal frame shift a paternal frame shift HMOX1 c.264_269delCTGG (p.L89Sfs*24) and maternal splice donor HMOX1 (c.636 + 2 T > A) consistent with HMOX1 deficiency. Western blot analysis confirmed lack of HMOX1 protein upon oxidant stimulation of the patient cells. CONCLUSIONS: Here, we describe a phenotype expansion for HMOX1-deficiency to include not only asplenia and hepatomegaly, but also interstitial lung disease with cholesterol granulomas and inflammatory flares with hemophagocytosis present in the bone marrow.

Heterozygous Gene Deficiency and Risk of Coronary Artery Disease. - Nomura, Akihiro; Emdin, Connor A; Won, Hong Hee; Peloso, Gina M; Natarajan, Pradeep; Ardissino, Diego; Danesh, John; Schunkert, Heribert; Correa, Adolfo; Bown, Matthew J; Samani, Nilesh J; Erdmann, Jeanette; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: Familial sitosterolemia is a rare Mendelian disorder characterized by hyperabsorption and decreased biliary excretion of dietary sterols. Affected individuals typically have complete genetic deficiency-homozygous loss-of-function (LoF) variants-in the or genes and have substantially elevated plasma sitosterol and LDL (low-density lipoprotein) cholesterol (LDL-C) levels. The impact of partial genetic deficiency of or -as occurs in heterozygous carriers of LoF variants-on LDL-C and risk of coronary artery disease (CAD) has remained uncertain. METHODS: We first recruited 9 sitosterolemia families, identified causative LoF variants in or , and evaluated the associations of these or LoF variants with plasma phytosterols and lipid levels. We next assessed for LoF variants in or in CAD cases (n=29 321) versus controls (n=357 326). We tested the association of rare LoF variants in or with blood lipids and risk for CAD. Rare LoF variants were defined as protein-truncating variants with minor allele frequency <0.1% in or . RESULTS: In sitosterolemia families, 7 pedigrees harbored causative LoF variants in and 2 pedigrees in . Homozygous LoF variants in either or led to marked elevations in sitosterol and LDL-C. Of those sitosterolemia families, heterozygous carriers of LoF variants exhibited increased sitosterol and LDL-C levels compared with noncarriers. Within large-scale CAD case-control cohorts, prevalence of rare LoF variants in and in was ≈0.1% each. heterozygous LoF variant carriers had significantly elevated LDL-C levels (25 mg/dL [95% CI, 14-35]; =1.1×10) and were at 2-fold increased risk of CAD (odds ratio, 2.06 [95% CI, 1.27-3.35]; =0.004). By contrast, heterozygous LoF carrier status was not associated with increased LDL-C or risk of CAD. CONCLUSIONS: Although familial sitosterolemia is traditionally considered as a recessive disorder, we observed that heterozygous carriers of an LoF variant in had significantly increased sitosterol and LDL-C levels and a 2-fold increase in risk of CAD.

Heterozygous loss of WBP11 function causes multiple congenital defects in humans and mice. - Martin, Ella M M A; Enriquez, Annabelle; Sparrow, Duncan B; Humphreys, David T; McInerney-Leo, Aideen M; Leo, Paul J; Duncan, Emma L; Iyer, Kavitha R; Greasby, Joelene A; Ip, Eddie; Giannoulatou, Eleni; Sheng, Delicia; et al. (Hum Mol Genet, 2020)
The genetic causes of multiple congenital anomalies are incompletely understood. Here, we report novel heterozygous predicted loss-of-function (LoF) and predicted damaging missense variants in the WW domain binding protein 11 (WBP11) gene in seven unrelated families with a variety of overlapping congenital malformations, including cardiac, vertebral, tracheo-esophageal, renal and limb defects. WBP11 encodes a component of the spliceosome with the ability to activate pre-messenger RNA splicing. We generated a Wbp11 null allele in mouse using CRISPR-Cas9 targeting. Wbp11 homozygous null embryos die prior to E8.5, indicating that Wbp11 is essential for development. Fewer Wbp11 heterozygous null mice are found than expected due to embryonic and postnatal death. Importantly, Wbp11 heterozygous null mice are small and exhibit defects in axial skeleton, kidneys and esophagus, similar to the affected individuals, supporting the role of WBP11 haploinsufficiency in the development of congenital malformations in humans. LoF WBP11 variants should be considered as a possible cause of VACTERL association as well as isolated Klippel-Feil syndrome, renal agenesis or esophageal atresia.

Human and mouse studies establish TBX6 in Mendelian CAKUT and as a potential driver of kidney defects associated with the 16p11.2 microdeletion syndrome. - Yang, Nan; Wu, Nan; Dong, Shuangshuang; Zhang, Ling; Zhao, Yanxue; Chen, Weisheng; Du, Renqian; Song, Chengcheng; Ren, Xiaojun; Liu, Jiaqi; Pehlivan, Davut; Liu, Zhenlei; et al. (Kidney Int, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUTs) are the most common cause of chronic kidney disease in children. Human 16p11.2 deletions have been associated with CAKUT, but the responsible molecular mechanism remains to be illuminated. To explore this, we investigated 102 carriers of 16p11.2 deletion from multi-center cohorts, among which we retrospectively ascertained kidney morphologic and functional data from 37 individuals (12 Chinese and 25 Caucasian/Hispanic). Significantly higher CAKUT rates were observed in 16p11.2 deletion carriers (about 25% in Chinese and 16% in Caucasian/Hispanic) than those found in the non-clinically ascertained general populations (about 1/1000 found at autopsy). Furthermore, we identified seven additional individuals with heterozygous loss-of-function variants in TBX6, a gene that maps to the 16p11.2 region. Four of these seven cases showed obvious CAKUT. To further investigate the role of TBX6 in kidney development, we engineered mice with mutated Tbx6 alleles. The Tbx6 heterozygous null (i.e., loss-of-function) mutant (Tbx6) resulted in 13% solitary kidneys. Remarkably, this incidence increased to 29% in a compound heterozygous model (Tbx6) that reduced Tbx6 gene dosage to below haploinsufficiency, by combining the null allele with a novel mild hypomorphic allele (mh). Renal hypoplasia was also frequently observed in these Tbx6-mutated mouse models. Thus, our findings in patients and mice establish TBX6 as a novel gene involved in CAKUT and its gene dosage insufficiency as a potential driver for kidney defects observed in the 16p11.2 microdeletion syndrome.

Human CRY1 variants associate with attention deficit/hyperactivity disorder. - Onat, O Emre; Kars, M Ece; Gül, Şeref; Bilguvar, Kaya; Wu, Yiming; Özhan, Ayşe; Aydın, Cihan; Başak, A Nazlı; Trusso, M Allegra; Goracci, Arianna; Fallerini, Chiara; Renieri, Alessandra; et al. (J Clin Invest, 2020)
Attention deficit/hyperactivity disorder (ADHD) is a common and heritable phenotype frequently accompanied by insomnia, anxiety, and depression. Here, using a reverse phenotyping approach, we report heterozygous coding variations in the core circadian clock gene cryptochrome 1 in 15 unrelated multigenerational families with combined ADHD and insomnia. The variants led to functional alterations in the circadian molecular rhythms, providing a mechanistic link to the behavioral symptoms. One variant, CRY1Δ11 c.1657+3A>C, is present in approximately 1% of Europeans, therefore standing out as a diagnostic and therapeutic marker. We showed by exome sequencing in an independent cohort of patients with combined ADHD and insomnia that 8 of 62 patients and 0 of 369 controls carried CRY1Δ11. Also, we identified a variant, CRY1Δ6 c.825+1G>A, that shows reduced affinity for BMAL1/CLOCK and causes an arrhythmic phenotype. Genotype-phenotype correlation analysis revealed that this variant segregated with ADHD and delayed sleep phase disorder (DSPD) in the affected family. Finally, we found in a phenome-wide association study involving 9438 unrelated adult Europeans that CRY1Δ11 was associated with major depressive disorder, insomnia, and anxiety. These results defined a distinctive group of circadian psychiatric phenotypes that we propose to designate as "circiatric" disorders.
Keywords: Adult; ARNTL Transcription Factors; Attention Deficit Disorder with Hyperactivity; CLOCK Proteins; Cryptochromes; Female; Genetic Association Studies; HEK293 Cells; Humans; Male; Mutation; Sleep Disorders, Circadian Rhythm

Human NK cell deficiency as a result of biallelic mutations in MCM10. - Mace, Emily M; Paust, Silke; Conte, Matilde I; Baxley, Ryan M; Schmit, Megan M; Patil, Sagar L; Guilz, Nicole C; Mukherjee, Malini; Pezzi, Ashley E; Chmielowiec, Jolanta; Tatineni, Swetha; Chinn, Ivan K; et al. (J Clin Invest, 2020)
Human natural killer cell deficiency (NKD) arises from inborn errors of immunity that lead to impaired NK cell development, function, or both. Through the understanding of the biological perturbations in individuals with NKD, requirements for the generation of terminally mature functional innate effector cells can be elucidated. Here, we report a cause of NKD resulting from compound heterozygous mutations in minichromosomal maintenance complex member 10 (MCM10) that impaired NK cell maturation in a child with fatal susceptibility to CMV. MCM10 has not been previously associated with monogenic disease and plays a critical role in the activation and function of the eukaryotic DNA replisome. Through evaluation of patient primary fibroblasts, modeling patient mutations in fibroblast cell lines, and MCM10 knockdown in human NK cell lines, we have shown that loss of MCM10 function leads to impaired cell cycle progression and induction of DNA damage-response pathways. By modeling MCM10 deficiency in primary NK cell precursors, including patient-derived induced pluripotent stem cells, we further demonstrated that MCM10 is required for NK cell terminal maturation and acquisition of immunological system function. Together, these data define MCM10 as an NKD gene and provide biological insight into the requirement for the DNA replisome in human NK cell maturation and function.
Keywords: Alleles; Cell Cycle Checkpoints; Cell Differentiation; Cell Line; Codon, Nonsense; DNA Damage; Fatal Outcome; Female; Gene Knockdown Techniques; Heterozygote; Humans; Induced Pluripotent Stem Cells; Infant; Killer Cells, Natural; Male; Minichromosome Maintenance Proteins; Models, Immunological; Mutation; Mutation, Missense; Pedigree; Primary Immunodeficiency Diseases

Identification of genetic variants in CFAP221 as a cause of primary ciliary dyskinesia. - Bustamante-Marin, Ximena M; Shapiro, Adam; Sears, Patrick R; Charng, Wu-Lin; Conrad, Donald F; Leigh, Margaret W; Knowles, Michael R; Ostrowski, Lawrence E; Zariwala, Maimoona A (J Hum Genet, 2020)
Primary ciliary dyskinesia (PCD) is a rare disorder that affects the biogenesis or function of motile cilia resulting in chronic airway disease. PCD is genetically and phenotypically heterogeneous, with causative mutations identified in over 40 genes; however, the genetic basis of many cases is unknown. Using whole-exome sequencing, we identified three affected siblings with clinical symptoms of PCD but normal ciliary structure, carrying compound heterozygous loss-of-function variants in CFAP221. Computational analysis suggests that these variants are the most damaging alleles shared by all three siblings. Nasal epithelial cells from one of the subjects demonstrated slightly reduced beat frequency (16.5 Hz vs 17.7 Hz, p = 0.16); however, waveform analysis revealed that the CFAP221 defective cilia beat in an aberrant circular pattern. These results show that genetic variants in CFAP221 cause PCD and that CFAP221 should be considered a candidate gene in cases where PCD is suspected but cilia structure and beat frequency appear normal.
Keywords: Alleles; Calmodulin-Binding Proteins; Cilia; Ciliary Motility Disorders; Epithelial Cells; Exons; Genetic Variation; Humans; Mutation; Proteins; Whole Exome Sequencing

Immunodeficiency, centromeric instability, and facial anomalies (ICF) syndrome with NK dysfunction and EBV-driven malignancy treated with stem cell transplantation. - Burk, Caitlin M; Coffey, Kara E; Mace, Emily M; Bostwick, Bret L; Chinn, Ivan K; Coban-Akdemir, Zeynep H; Jhangiani, Shalini N; Lupski, James R; Ortiz, Damara; Barnum, Jessie L; Allen, Steven W; Robertson, Leanna-Marie; et al. (J Allergy Clin Immunol Pract, 2020)
Keywords: Herpesvirus 4, Human; Humans; Immunologic Deficiency Syndromes; Mutation; Neoplasms; Primary Immunodeficiency Diseases; Stem Cell Transplantation

The impact of sex on gene expression across human tissues. - Oliva, Meritxell; Muñoz-Aguirre, Manuel; Kim-Hellmuth, Sarah; Wucher, Valentin; Gewirtz, Ariel D H; Cotter, Daniel J; Parsana, Princy; Kasela, Silva; Balliu, Brunilda; Viñuela, Ana; Castel, Stephane E; Mohammadi, Pejman; et al. (Science, 2020)
Many complex human phenotypes exhibit sex-differentiated characteristics. However, the molecular mechanisms underlying these differences remain largely unknown. We generated a catalog of sex differences in gene expression and in the genetic regulation of gene expression across 44 human tissue sources surveyed by the Genotype-Tissue Expression project (GTEx, v8 release). We demonstrate that sex influences gene expression levels and cellular composition of tissue samples across the human body. A total of 37% of all genes exhibit sex-biased expression in at least one tissue. We identify cis expression quantitative trait loci (eQTLs) with sex-differentiated effects and characterize their cellular origin. By integrating sex-biased eQTLs with genome-wide association study data, we identify 58 gene-trait associations that are driven by genetic regulation of gene expression in a single sex. These findings provide an extensive characterization of sex differences in the human transcriptome and its genetic regulation.
Keywords: Chromosomes, Human, X; Disease; Epigenesis, Genetic; Female; Gene Expression; Gene Expression Regulation; Genetic Variation; Genome-Wide Association Study; Humans; Male; Organ Specificity; Promoter Regions, Genetic; Quantitative Trait Loci; Sex Characteristics; Sex Factors

Inborn errors of type I IFN immunity in patients with life-threatening COVID-19. - Zhang, Qian; Bastard, Paul; Liu, Zhiyong; Le Pen, Jérémie; Moncada-Velez, Marcela; Chen, Jie; Ogishi, Masato; Sabli, Ira K D; Hodeib, Stephanie; Korol, Cecilia; Rosain, Jérémie; Bilguvar, Kaya; et al. (Science, 2020)
Clinical outcome upon infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ranges from silent infection to lethal coronavirus disease 2019 (COVID-19). We have found an enrichment in rare variants predicted to be loss-of-function (LOF) at the 13 human loci known to govern Toll-like receptor 3 (TLR3)- and interferon regulatory factor 7 (IRF7)-dependent type I interferon (IFN) immunity to influenza virus in 659 patients with life-threatening COVID-19 pneumonia relative to 534 subjects with asymptomatic or benign infection. By testing these and other rare variants at these 13 loci, we experimentally defined LOF variants underlying autosomal-recessive or autosomal-dominant deficiencies in 23 patients (3.5%) 17 to 77 years of age. We show that human fibroblasts with mutations affecting this circuit are vulnerable to SARS-CoV-2. Inborn errors of TLR3- and IRF7-dependent type I IFN immunity can underlie life-threatening COVID-19 pneumonia in patients with no prior severe infection.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Asymptomatic Infections; Betacoronavirus; Child; Child, Preschool; Coronavirus Infections; COVID-19; Female; Genetic Loci; Genetic Predisposition to Disease; Humans; Infant; Interferon Regulatory Factor-7; Interferon Type I; Loss of Function Mutation; Male; Middle Aged; Pandemics; Pneumonia, Viral; Receptor, Interferon alpha-beta; SARS-CoV-2; Toll-Like Receptor 3; Young Adult

Increased gene dosages induce congenital cervical vertebral malformations in humans and mice. - Ren, Xiaojun; Yang, Nan; Wu, Nan; Xu, Ximing; Chen, Weisheng; Zhang, Ling; Li, Yingping; Du, Ren-Qian; Dong, Shuangshuang; Zhao, Sen; Chen, Shuxia; Jiang, Li-Ping; et al. (J Med Genet, 2020)
BACKGROUND: Congenital vertebral malformations (CVMs) manifest with abnormal vertebral morphology. Genetic factors have been implicated in CVM pathogenesis, but the underlying pathogenic mechanisms remain unclear in most subjects. We previously reported that the human 16p11.2 BP4-BP5 deletion and its associated dosage reduction caused CVMs. We aim to investigate the reciprocal 16p11.2 BP4-BP5 duplication and its potential genetic contributions to CVMs. METHODS AND RESULTS: Patients who were found to carry the 16p11.2 BP4-BP5 duplication by chromosomal microarray analysis were retrospectively analysed for their vertebral phenotypes. The spinal assessments in seven duplication carriers showed that four (57%) presented characteristics of CVMs, supporting the contention that increased dosage could induce CVMs. For further in vivo functional investigation in a model organism, we conducted genome editing of the upstream regulatory region of mouse using CRISPR-Cas9 and obtained three mouse mutant alleles ( to ) with elevated expression levels of . Luciferase reporter assays showed that the allele presented with the 160% expression level of that observed in the reference (+) allele. Therefore, the homozygous mice could functionally mimic the dosage of heterozygous carriers of 16p11.2 BP4-BP5 duplication (approximately 150%, ie, 3/2 gene dosage of the normal level). Remarkably, 60% of the mice manifested with CVMs. Consistent with our observations in humans, the CVMs induced by increased dosage in mice mainly affected the cervical vertebrae. CONCLUSION: Our findings in humans and mice consistently support that an increased dosage contributes to the risk of developing cervical CVMs.

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.
Keywords: Adult; Africa; African Continental Ancestry Group; Aged; Aged, 80 and over; alpha Karyopherins; Cell Self Renewal; Clonal Hematopoiesis; DNA-Binding Proteins; Female; Genetic Predisposition to Disease; Genome, Human; Germ-Line Mutation; Hematopoietic Stem Cells; Humans; Intracellular Signaling Peptides and Proteins; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Proto-Oncogene Proteins; Tripartite Motif Proteins; United States; Whole Genome Sequencing

Inherited glomerular diseases in the gilded age of genomic advancements. - Gulati, Ashima; Dahl, Neera; Tufro, Alda (Pediatr Nephrol, 2020)
The synchronized advent of high-throughput next-generation sequencing technology and knowledge of the human genome has rendered exponential contributions to our understanding of the pathophysiology of glomerular kidney diseases. A genetic diagnosis can now be made or confirmed in about two-thirds of the suspected inherited glomerular diseases. Next-generation sequencing is adept at identifying single nucleotide variations and small insertions or deletions that constitute majority of the disease-causing mutations. Description of the complete mutation spectrum in syndromic glomerulopathies may require the use of both sequencing and cytogenetic methods to detect large structural DNA variation in addition to single nucleotide changes. The enthusiastic application of genetic and genomic knowledge to inherited glomerular diseases has uncovered anticipated and unforeseen challenges mainly related to the biological interpretation of variants of uncertain significance and the limited benefit on clinical management for the individual patient when a diagnosis is obtained. To attain the ultimate goal of transforming clinical decision-making based on accurate genetic diagnosis using genomic information, these challenges need to be addressed. Till then, the glory of genomic medicine stands the test of time in this gilded age of genomic advancements.
Keywords: Adolescent; Age Factors; Branchio-Oto-Renal Syndrome; Child; Female; High-Throughput Nucleotide Sequencing; Humans; Infant; Kidney Failure, Chronic; Male; Middle Aged; Mutation; Pedigree; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Whole Exome Sequencing

KIAA1217: A novel candidate gene associated with isolated and syndromic vertebral malformations. - Al Dhaheri, Noura; Wu, Nan; Zhao, Sen; Wu, Zhihong; Blank, Robert D; Zhang, Jianguo; Raggio, Cathy; Halanski, Matthew; Shen, Jianxiong; Noonan, Ken; Qiu, Guixing; Nemeth, Blaise; et al. (Am J Med Genet A, 2020)
Vertebral malformations (VMs) are caused by alterations in somitogenesis and may occur in association with other congenital anomalies. The genetic etiology of most VMs remains unknown and their identification may facilitate the development of novel therapeutic and prevention strategies. Exome sequencing was performed on both the discovery cohort of nine unrelated probands from the USA with VMs and the replication cohort from China (Deciphering Disorders Involving Scoliosis & COmorbidities study). The discovery cohort was analyzed using the PhenoDB analysis tool. Heterozygous and homozygous, rare and functional variants were selected and evaluated for their ClinVar, HGMD, OMIM, GWAS, mouse model phenotypes, and other annotations to identify the best candidates. Genes with candidate variants in three or more probands were selected. The replication cohort was analyzed by another in-house developed pipeline. We identified rare heterozygous variants in KIAA1217 in four out of nine probands in the discovery cohort and in five out of 35 probands in the replication cohort. Collectively, we identified 11 KIAA1217 rare variants in 10 probands, three of which have not been described in gnomAD and one of which is a nonsense variant. We propose that genetic variations of KIAA1217 may contribute to the etiology of VMs.
Keywords: Adolescent; Cervical Vertebrae; Child; Codon, Nonsense; Databases, Genetic; Female; Heterozygote; Homozygote; Humans; Male; Proteins; Spinal Diseases; Thoracic Vertebrae

KMT2B-related disorders: expansion of the phenotypic spectrum and long-term efficacy of deep brain stimulation. - Cif, Laura; Demailly, Diane; Lin, Jean-Pierre; Barwick, Katy E; Sa, Mario; Abela, Lucia; Malhotra, Sony; Chong, Wui K; Steel, Dora; Sanchis-Juan, Alba; Ngoh, Adeline; Trump, Natalie; et al. (Brain, 2020)
Heterozygous mutations in KMT2B are associated with an early-onset, progressive and often complex dystonia (DYT28). Key characteristics of typical disease include focal motor features at disease presentation, evolving through a caudocranial pattern into generalized dystonia, with prominent oromandibular, laryngeal and cervical involvement. Although KMT2B-related disease is emerging as one of the most common causes of early-onset genetic dystonia, much remains to be understood about the full spectrum of the disease. We describe a cohort of 53 patients with KMT2B mutations, with detailed delineation of their clinical phenotype and molecular genetic features. We report new disease presentations, including atypical patterns of dystonia evolution and a subgroup of patients with a non-dystonic neurodevelopmental phenotype. In addition to the previously reported systemic features, our study has identified co-morbidities, including the risk of status dystonicus, intrauterine growth retardation, and endocrinopathies. Analysis of this study cohort (n = 53) in tandem with published cases (n = 80) revealed that patients with chromosomal deletions and protein truncating variants had a significantly higher burden of systemic disease (with earlier onset of dystonia) than those with missense variants. Eighteen individuals had detailed longitudinal data available after insertion of deep brain stimulation for medically refractory dystonia. Median age at deep brain stimulation was 11.5 years (range: 4.5-37.0 years). Follow-up after deep brain stimulation ranged from 0.25 to 22 years. Significant improvement of motor function and disability (as assessed by the Burke Fahn Marsden's Dystonia Rating Scales, BFMDRS-M and BFMDRS-D) was evident at 6 months, 1 year and last follow-up (motor, P = 0.001, P = 0.004, and P = 0.012; disability, P = 0.009, P = 0.002 and P = 0.012). At 1 year post-deep brain stimulation, >50% of subjects showed BFMDRS-M and BFMDRS-D improvements of >30%. In the long-term deep brain stimulation cohort (deep brain stimulation inserted for >5 years, n = 8), improvement of >30% was maintained in 5/8 and 3/8 subjects for the BFMDRS-M and BFMDRS-D, respectively. The greatest BFMDRS-M improvements were observed for trunk (53.2%) and cervical (50.5%) dystonia, with less clinical impact on laryngeal dystonia. Improvements in gait dystonia decreased from 20.9% at 1 year to 16.2% at last assessment; no patient maintained a fully independent gait. Reduction of BFMDRS-D was maintained for swallowing (52.9%). Five patients developed mild parkinsonism following deep brain stimulation. KMT2B-related disease comprises an expanding continuum from infancy to adulthood, with early evidence of genotype-phenotype correlations. Except for laryngeal dysphonia, deep brain stimulation provides a significant improvement in quality of life and function with sustained clinical benefit depending on symptoms distribution.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosome Deletion; Cohort Studies; Computer Simulation; Deep Brain Stimulation; Disease Progression; Dystonic Disorders; Endocrine System Diseases; Female; Fetal Growth Retardation; Gait Disorders, Neurologic; Histone-Lysine N-Methyltransferase; Humans; Laryngeal Diseases; Male; Mutation; Mutation, Missense; Phenotype; Quality of Life; Treatment Outcome; Young Adult

Landscape of multi-nucleotide variants in 125,748 human exomes and 15,708 genomes. - Wang, Qingbo; Pierce-Hoffman, Emma; Cummings, Beryl B; Alföldi, Jessica; Francioli, Laurent C; Gauthier, Laura D; Hill, Andrew J; O'Donnell-Luria, Anne H; Karczewski, Konrad J; MacArthur, Daniel G (Nat Commun, 2020)
Multi-nucleotide variants (MNVs), defined as two or more nearby variants existing on the same haplotype in an individual, are a clinically and biologically important class of genetic variation. However, existing tools typically do not accurately classify MNVs, and understanding of their mutational origins remains limited. Here, we systematically survey MNVs in 125,748 whole exomes and 15,708 whole genomes from the Genome Aggregation Database (gnomAD). We identify 1,792,248 MNVs across the genome with constituent variants falling within 2 bp distance of one another, including 18,756 variants with a novel combined effect on protein sequence. Finally, we estimate the relative impact of known mutational mechanisms - CpG deamination, replication error by polymerase zeta, and polymerase slippage at repeat junctions - on the generation of MNVs. Our results demonstrate the value of haplotype-aware variant annotation, and refine our understanding of genome-wide mutational mechanisms of MNVs.
Keywords: CpG Islands; Databases, Genetic; DNA Mutational Analysis; Exome; Genetic Variation; Genome, Human; Humans; Mutation

Large-Scale Exome Sequencing Study Implicates Both Developmental and Functional Changes in the Neurobiology of Autism. - Satterstrom, F Kyle; Kosmicki, Jack A; Wang, Jiebiao; Breen, Michael S; De Rubeis, Silvia; An, Joon-Yong; Peng, Minshi; Collins, Ryan; Grove, Jakob; Klei, Lambertus; Stevens, Christine; Reichert, Jennifer; et al. (Cell, 2020)
We present the largest exome sequencing study of autism spectrum disorder (ASD) to date (n = 35,584 total samples, 11,986 with ASD). Using an enhanced analytical framework to integrate de novo and case-control rare variation, we identify 102 risk genes at a false discovery rate of 0.1 or less. Of these genes, 49 show higher frequencies of disruptive de novo variants in individuals ascertained to have severe neurodevelopmental delay, whereas 53 show higher frequencies in individuals ascertained to have ASD; comparing ASD cases with mutations in these groups reveals phenotypic differences. Expressed early in brain development, most risk genes have roles in regulation of gene expression or neuronal communication (i.e., mutations effect neurodevelopmental and neurophysiological changes), and 13 fall within loci recurrently hit by copy number variants. In cells from the human cortex, expression of risk genes is enriched in excitatory and inhibitory neuronal lineages, consistent with multiple paths to an excitatory-inhibitory imbalance underlying ASD.
Keywords: Autistic Disorder; Case-Control Studies; Cell Lineage; Cerebral Cortex; Cohort Studies; Exome; Female; Gene Expression Regulation, Developmental; Gene Frequency; Genetic Predisposition to Disease; Humans; Male; Mutation, Missense; Neurobiology; Neurons; Phenotype; Sex Factors; Single-Cell Analysis; Whole Exome Sequencing

Likely damaging de novo variants in congenital diaphragmatic hernia patients are associated with worse clinical outcomes. - Qiao, Lu; Wynn, Julia; Yu, Lan; Hernan, Rebecca; Zhou, Xueya; Duron, Vincent; Aspelund, Gudrun; Farkouh-Karoleski, Christiana; Zygumunt, Annette; Krishnan, Usha S; Nees, Shannon; Khlevner, Julie; et al. (Genet Med, 2020)
PURPOSE: Congenital diaphragmatic hernia (CDH) is associated with significant mortality and long-term morbidity in some but not all individuals. We hypothesize monogenic factors that cause CDH are likely to have pleiotropic effects and be associated with worse clinical outcomes. METHODS: We enrolled and prospectively followed 647 newborns with CDH and performed genomic sequencing on 462 trios to identify de novo variants. We grouped cases into those with and without likely damaging (LD) variants and systematically assessed CDH clinical outcomes between the genetic groups. RESULTS: Complex cases with additional congenital anomalies had higher mortality than isolated cases (P = 8 × 10). Isolated cases with LD variants had similar mortality to complex cases and much higher mortality than isolated cases without LD (P = 3 × 10). The trend was similar with pulmonary hypertension at 1 month. Cases with LD variants had an estimated 12-17 points lower scores on neurodevelopmental assessments at 2 years compared with cases without LD variants, and this difference is similar in isolated and complex cases. CONCLUSION: We found that the LD genetic variants are associated with higher mortality, worse pulmonary hypertension, and worse neurodevelopment outcomes compared with non-LD variants. Our results have important implications for prognosis, potential intervention and long-term follow up for children with CDH.
Keywords: Child; Hernias, Diaphragmatic, Congenital; Humans; Infant, Newborn; Retrospective Studies

Loss of CBY1 results in a ciliopathy characterized by features of Joubert syndrome. - Epting, Daniel; Senaratne, Lokuliyange D S; Ott, Elisabeth; Holmgren, Asbjørn; Sumathipala, Dulika; Larsen, Selma M; Wallmeier, Julia; Bracht, Diana; Frikstad, Kari-Anne M; Crowley, Suzanne; Sikiric, Alma; Barøy, Tuva; et al. (Hum Mutat, 2020)
Ciliopathies are clinically and genetically heterogeneous diseases. We studied three patients from two independent families presenting with features of Joubert syndrome: abnormal breathing pattern during infancy, developmental delay/intellectual disability, cerebellar ataxia, molar tooth sign on magnetic resonance imaging scans, and polydactyly. We identified biallelic loss-of-function (LOF) variants in CBY1, segregating with the clinical features of Joubert syndrome in the families. CBY1 localizes to the distal end of the mother centriole, contributing to the formation and function of cilia. In accordance with the clinical and mutational findings in the affected individuals, we demonstrated that depletion of Cby1 in zebrafish causes ciliopathy-related phenotypes. Levels of CBY1 transcript were found reduced in the patients compared with controls, suggesting degradation of the mutated transcript through nonsense-mediated messenger RNA decay. Accordingly, we could detect CBY1 protein in fibroblasts from controls, but not from patients by immunofluorescence. Furthermore, we observed reduced ability to ciliate, increased ciliary length, and reduced levels of the ciliary proteins AHI1 and ARL13B in patient fibroblasts. Our data show that CBY1 LOF-variants cause a ciliopathy with features of Joubert syndrome.

Loss of NARS1 impairs progenitor proliferation in cortical brain organoids and leads to microcephaly. - Wang, Lu; Li, Zhen; Sievert, David; Smith, Desirée E C; Mendes, Marisa I; Chen, Dillon Y; Stanley, Valentina; Ghosh, Shereen; Wang, Yulu; Kara, Majdi; Aslanger, Ayca Dilruba; Rosti, Rasim O; et al. (Nat Commun, 2020)
Asparaginyl-tRNA synthetase1 (NARS1) is a member of the ubiquitously expressed cytoplasmic Class IIa family of tRNA synthetases required for protein translation. Here, we identify biallelic missense and frameshift mutations in NARS1 in seven patients from three unrelated families with microcephaly and neurodevelopmental delay. Patient cells show reduced NARS1 protein, impaired NARS1 activity and impaired global protein synthesis. Cortical brain organoid modeling shows reduced proliferation of radial glial cells (RGCs), leading to smaller organoids characteristic of microcephaly. Single-cell analysis reveals altered constituents of both astrocytic and RGC lineages, suggesting a requirement for NARS1 in RGC proliferation. Our findings demonstrate that NARS1 is required to meet protein synthetic needs and to support RGC proliferation in human brain development.
Keywords: Adolescent; Adult; Aspartate-tRNA Ligase; Base Sequence; Cell Differentiation; Cell Proliferation; Cell Size; Cell Survival; Cerebral Cortex; Child; Family; Female; Fibroblasts; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Ki-67 Antigen; Male; Microcephaly; Mutation; Neural Stem Cells; Neuroglia; Organoids; Pedigree; RNA, Transfer, Amino Acyl; Young Adult

Loss of the neural-specific BAF subunit ACTL6B relieves repression of early response genes and causes recessive autism. - Wenderski, Wendy; Wang, Lu; Krokhotin, Andrey; Walsh, Jessica J; Li, Hongjie; Shoji, Hirotaka; Ghosh, Shereen; George, Renee D; Miller, Erik L; Elias, Laura; Gillespie, Mark A; Son, Esther Y; et al. (Proc Natl Acad Sci U S A, 2020)
Synaptic activity in neurons leads to the rapid activation of genes involved in mammalian behavior. ATP-dependent chromatin remodelers such as the BAF complex contribute to these responses and are generally thought to activate transcription. However, the mechanisms keeping such "early activation" genes silent have been a mystery. In the course of investigating Mendelian recessive autism, we identified six families with segregating loss-of-function mutations in the neuronal BAF (nBAF) subunit (originally named ). Accordingly, was the most significantly mutated gene in the Simons Recessive Autism Cohort. At least 14 subunits of the nBAF complex are mutated in autism, collectively making it a major contributor to autism spectrum disorder (ASD). Patient mutations destabilized ACTL6B protein in neurons and rerouted dendrites to the wrong glomerulus in the fly olfactory system. Humans and mice lacking showed corpus callosum hypoplasia, indicating a conserved role for in facilitating neural connectivity. knockout mice on two genetic backgrounds exhibited ASD-related behaviors, including social and memory impairments, repetitive behaviors, and hyperactivity. Surprisingly, mutation of relieved repression of early response genes including AP1 transcription factors (, , , and ), increased chromatin accessibility at AP1 binding sites, and transcriptional changes in late response genes associated with early response transcription factor activity. loss is thus an important cause of recessive ASD, with impaired neuron-specific chromatin repression indicated as a potential mechanism.
Keywords: Actins; Adenosine Triphosphate; Animals; Autism Spectrum Disorder; Behavior, Animal; Chromatin; Chromatin Assembly and Disassembly; Chromosomal Proteins, Non-Histone; Chromosome Pairing; Corpus Callosum; Dendrites; Disease Models, Animal; DNA-Binding Proteins; Gene Expression Regulation; Hippocampus; Humans; Mice; Mice, Knockout; Mutation; Neurons; Transcription Factors

Low-level parental somatic mosaic SNVs in exomes from a large cohort of trios with diverse suspected Mendelian conditions. - Gambin, Tomasz; Liu, Qian; Karolak, Justyna A; Grochowski, Christopher M; Xie, Nina G; Wu, Lucia R; Yan, Yan Helen; Cao, Ye; Coban Akdemir, Zeynep H; Wilson, Theresa A; Jhangiani, Shalini N; Chen, Ed; et al. (Genet Med, 2020)
PURPOSE: The goal of this study was to assess the scale of low-level parental mosaicism in exome sequencing (ES) databases. METHODS: We analyzed approximately 2000 family trio ES data sets from the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) and Baylor Genetics (BG). Among apparent de novo single-nucleotide variants identified in the affected probands, we selected rare unique variants with variant allele fraction (VAF) between 30% and 70% in the probands and lower than 10% in one of the parents. RESULTS: Of 102 candidate mosaic variants validated using amplicon-based next-generation sequencing, droplet digital polymerase chain reaction, or blocker displacement amplification, 27 (26.4%) were confirmed to be low- (VAF between 1% and 10%) or very low (VAF <1%) level mosaic. Detection precision in parental samples with two or more alternate reads was 63.6% (BHCMG) and 43.6% (BG). In nine investigated individuals, we observed variability of mosaic ratios among blood, saliva, fibroblast, buccal, hair, and urine samples. CONCLUSION: Our computational pipeline enables robust discrimination between true and false positive candidate mosaic variants and efficient detection of low-level mosaicism in ES samples. We confirm that the presence of two or more alternate reads in the parental sample is a reliable predictor of low-level parental somatic mosaicism.
Keywords: Exome; High-Throughput Nucleotide Sequencing; Humans; Mosaicism; Parents; Whole Exome Sequencing

Lung Function in African American Children with Asthma Is Associated with Novel Regulatory Variants of the KIT Ligand and Gene-By-Air-Pollution Interaction. - Mak, Angel C Y; Sajuthi, Satria; Joo, Jaehyun; Xiao, Shujie; Sleiman, Patrick M; White, Marquitta J; Lee, Eunice Y; Saef, Benjamin; Hu, Donglei; Gui, Hongsheng; Keys, Kevin L; Lurmann, Fred; et al. (Genetics, 2020)
Baseline lung function, quantified as forced expiratory volume in the first second of exhalation (FEV), is a standard diagnostic criterion used by clinicians to identify and classify lung diseases. Using whole-genome sequencing data from the National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine project, we identified a novel genetic association with FEV on chromosome 12 in 867 African American children with asthma ( = 1.26 × 10, β = 0.302). Conditional analysis within 1 Mb of the tag signal (rs73429450) yielded one major and two other weaker independent signals within this peak. We explored statistical and functional evidence for all variants in linkage disequilibrium with the three independent signals and yielded nine variants as the most likely candidates responsible for the association with FEV Hi-C data and expression QTL analysis demonstrated that these variants physically interacted with (KIT ligand, also known as ), and their minor alleles were associated with increased expression of the gene in nasal epithelial cells. Gene-by-air-pollution interaction analysis found that the candidate variant rs58475486 interacted with past-year ambient sulfur dioxide exposure ( = 0.003, β = 0.32). This study identified a novel protective genetic association with FEV, possibly mediated through , in African American children with asthma. This is the first study that has identified a genetic association between lung function and , which has established a role in orchestrating allergic inflammation in asthma.

Major Impacts of Widespread Structural Variation on Gene Expression and Crop Improvement in Tomato. - Alonge, Michael; Wang, Xingang; Benoit, Matthias; Soyk, Sebastian; Pereira, Lara; Zhang, Lei; Suresh, Hamsini; Ramakrishnan, Srividya; Maumus, Florian; Ciren, Danielle; Levy, Yuval; Harel, Tom Hai; et al. (Cell, 2020)
Structural variants (SVs) underlie important crop improvement and domestication traits. However, resolving the extent, diversity, and quantitative impact of SVs has been challenging. We used long-read nanopore sequencing to capture 238,490 SVs in 100 diverse tomato lines. This panSV genome, along with 14 new reference assemblies, revealed large-scale intermixing of diverse genotypes, as well as thousands of SVs intersecting genes and cis-regulatory regions. Hundreds of SV-gene pairs exhibit subtle and significant expression changes, which could broadly influence quantitative trait variation. By combining quantitative genetics with genome editing, we show how multiple SVs that changed gene dosage and expression levels modified fruit flavor, size, and production. In the last example, higher order epistasis among four SVs affecting three related transcription factors allowed introduction of an important harvesting trait in modern tomato. Our findings highlight the underexplored role of SVs in genotype-to-phenotype relationships and their widespread importance and utility in crop improvement.
Keywords: Alleles; Crops, Agricultural; Cytochrome P-450 Enzyme System; Ecotype; Epistasis, Genetic; Fruit; Gene Duplication; Gene Expression Regulation, Plant; Genome, Plant; Genomic Structural Variation; Genotype; Inbreeding; Lycopersicon esculentum; Molecular Sequence Annotation; Phenotype; Plant Breeding; Quantitative Trait Loci

Mapping and characterization of structural variation in 17,795 human genomes. - Abel, Haley J; Larson, David E; Regier, Allison A; Chiang, Colby; Das, Indraniel; Kanchi, Krishna L; Layer, Ryan M; Neale, Benjamin M; Salerno, William J; Reeves, Catherine; Buyske, Steven; Matise, Tara C; et al. (Nature, 2020)
A key goal of whole-genome sequencing for studies of human genetics is to interrogate all forms of variation, including single-nucleotide variants, small insertion or deletion (indel) variants and structural variants. However, tools and resources for the study of structural variants have lagged behind those for smaller variants. Here we used a scalable pipeline to map and characterize structural variants in 17,795 deeply sequenced human genomes. We publicly release site-frequency data to create the largest, to our knowledge, whole-genome-sequencing-based structural variant resource so far. On average, individuals carry 2.9 rare structural variants that alter coding regions; these variants affect the dosage or structure of 4.2 genes and account for 4.0-11.2% of rare high-impact coding alleles. Using a computational model, we estimate that structural variants account for 17.2% of rare alleles genome-wide, with predicted deleterious effects that are equivalent to loss-of-function coding alleles; approximately 90% of such structural variants are noncoding deletions (mean 19.1 per genome). We report 158,991 ultra-rare structural variants and show that 2% of individuals carry ultra-rare megabase-scale structural variants, nearly half of which are balanced or complex rearrangements. Finally, we infer the dosage sensitivity of genes and noncoding elements, and reveal trends that relate to element class and conservation. This work will help to guide the analysis and interpretation of structural variants in the era of whole-genome sequencing.
Keywords: Alleles; Case-Control Studies; Continental Population Groups; Epigenesis, Genetic; Female; Gene Dosage; Genetic Variation; Genetics, Population; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Sequence Annotation; Quantitative Trait Loci; Software; Whole Genome Sequencing

Missed diagnoses: Clinically relevant lessons learned through medical mysteries solved by the Undiagnosed Diseases Network. - Cope, Heidi; Spillmann, Rebecca; Rosenfeld, Jill A; Brokamp, Elly; Signer, Rebecca; Schoch, Kelly; Kelley, Emily G; Sullivan, Jennifer A; Macnamara, Ellen; Lincoln, Sharyn; Golden-Grant, Katie; Orengo, James P; et al. (Mol Genet Genomic Med, 2020)
BACKGROUND: Resources within the Undiagnosed Diseases Network (UDN), such as genome sequencing (GS) and model organisms aid in diagnosis and identification of new disease genes, but are currently difficult to access by clinical providers. While these resources do contribute to diagnoses in many cases, they are not always necessary to reach diagnostic resolution. The UDN experience has been that participants can also receive diagnoses through the thoughtful and customized application of approaches and resources that are readily available in clinical settings. METHODS: The UDN Genetic Counseling and Testing Working Group collected case vignettes that illustrated how clinically available methods resulted in diagnoses. The case vignettes were classified into three themes; phenotypic considerations, selection of genetic testing, and evaluating exome/GS variants and data. RESULTS: We present 12 participants that illustrate how clinical practices such as phenotype-driven genomic investigations, consideration of variable expressivity, selecting the relevant tissue of interest for testing, utilizing updated testing platforms, and recognition of alternate transcript nomenclature resulted in diagnoses. CONCLUSION: These examples demonstrate that when a diagnosis is elusive, an iterative patient-specific approach utilizing assessment options available to clinical providers may solve a portion of cases. However, this does require increased provider time commitment, a particular challenge in the current practice of genomics.
Keywords: Adolescent; Child; Child, Preschool; Databases, Factual; Diagnosis, Computer-Assisted; Female; Genetic Diseases, Inborn; Genetic Testing; Humans; Information Dissemination; Male; Middle Aged; Missed Diagnosis; National Institutes of Health (U.S.); Phenotype; Precision Medicine; Undiagnosed Diseases; United States; Young Adult

A missense mutation in the catalytic domain of O-GlcNAc transferase links perturbations in protein O-GlcNAcylation to X-linked intellectual disability. - Pravata, Veronica M; Gundogdu, Mehmet; Bartual, Sergio G; Ferenbach, Andrew T; Stavridis, Marios; Õunap, Katrin; Pajusalu, Sander; Žordania, Riina; Wojcik, Monica H; van Aalten, Daan M F (FEBS Lett, 2020)
X-linked intellectual disabilities (XLID) are common developmental disorders. The enzyme O-GlcNAc transferase encoded by OGT, a recently discovered XLID gene, attaches O-GlcNAc to nuclear and cytoplasmic proteins. As few missense mutations have been described, it is unclear what the aetiology of the patient phenotypes is. Here, we report the discovery of a missense mutation in the catalytic domain of OGT in an XLID patient. X-ray crystallography reveals that this variant leads to structural rearrangements in the catalytic domain. The mutation reduces in vitro OGT activity on substrate peptides/protein. Mouse embryonic stem cells carrying the mutation reveal reduced O-GlcNAcase (OGA) and global O-GlcNAc levels. These data suggest a direct link between changes in the O-GlcNAcome and intellectual disability observed in patients carrying OGT mutations.
Keywords: Animals; Catalytic Domain; Cell Line; Glycosylation; Humans; Intellectual Disability; Mice; Models, Molecular; Mutation, Missense; N-Acetylglucosaminyltransferases

Missense variant contribution to USP9X-female syndrome. - Jolly, Lachlan A; Parnell, Euan; Gardner, Alison E; Corbett, Mark A; Pérez-Jurado, Luis A; Shaw, Marie; Lesca, Gaetan; Keegan, Catherine; Schneider, Michael C; Griffin, Emily; Maier, Felicitas; Kiss, Courtney; et al. (NPJ Genom Med, 2020)
USP9X is an X-chromosome gene that escapes X-inactivation. Loss or compromised function of USP9X leads to neurodevelopmental disorders in males and females. While males are impacted primarily by hemizygous partial loss-of-function missense variants, in females de novo heterozygous complete loss-of-function mutations predominate, and give rise to the clinically recognisable USP9X-female syndrome. Here we provide evidence of the contribution of USP9X missense and small in-frame deletion variants in USP9X-female syndrome also. We scrutinise the pathogenicity of eleven such variants, ten of which were novel. Combined application of variant prediction algorithms, protein structure modelling, and assessment under clinically relevant guidelines universally support their pathogenicity. The core phenotype of this cohort overlapped with previous descriptions of USP9X-female syndrome, but exposed heightened variability. Aggregate phenotypic information of 35 currently known females with predicted pathogenic variation in USP9X reaffirms the clinically recognisable USP9X-female syndrome, and highlights major differences when compared to USP9X-male associated neurodevelopmental disorders.

A missense variant in Mitochondrial Amidoxime Reducing Component 1 gene and protection against liver disease. - Emdin, Connor A; Haas, Mary E; Khera, Amit V; Aragam, Krishna; Chaffin, Mark; Klarin, Derek; Hindy, George; Jiang, Lan; Wei, Wei-Qi; Feng, Qiping; Karjalainen, Juha; Havulinna, Aki; et al. (PLoS Genet, 2020)
Analyzing 12,361 all-cause cirrhosis cases and 790,095 controls from eight cohorts, we identify a common missense variant in the Mitochondrial Amidoxime Reducing Component 1 gene (MARC1 p.A165T) that associates with protection from all-cause cirrhosis (OR 0.91, p = 2.3*10-11). This same variant also associates with lower levels of hepatic fat on computed tomographic imaging and lower odds of physician-diagnosed fatty liver as well as lower blood levels of alanine transaminase (-0.025 SD, 3.7*10-43), alkaline phosphatase (-0.025 SD, 1.2*10-37), total cholesterol (-0.030 SD, p = 1.9*10-36) and LDL cholesterol (-0.027 SD, p = 5.1*10-30) levels. We identified a series of additional MARC1 alleles (low-frequency missense p.M187K and rare protein-truncating p.R200Ter) that also associated with lower cholesterol levels, liver enzyme levels and reduced risk of cirrhosis (0 cirrhosis cases for 238 R200Ter carriers versus 17,046 cases of cirrhosis among 759,027 non-carriers, p = 0.04) suggesting that deficiency of the MARC1 enzyme may lower blood cholesterol levels and protect against cirrhosis.
Keywords: Alleles; Cholesterol, LDL; Coronary Artery Disease; Datasets as Topic; Fatty Liver; Female; Genetic Predisposition to Disease; Homozygote; Humans; Liver; Liver Cirrhosis; Liver Cirrhosis, Alcoholic; Loss of Function Mutation; Male; Middle Aged; Mitochondrial Proteins; Mutation, Missense; Oxidoreductases

MN1 C-terminal truncation syndrome is a novel neurodevelopmental and craniofacial disorder with partial rhombencephalosynapsis. - Mak, Christopher C Y; Doherty, Dan; Lin, Angela E; Vegas, Nancy; Cho, Megan T; Viot, Géraldine; Dimartino, Clémantine; Weisfeld-Adams, James D; Lessel, Davor; Joss, Shelagh; Li, Chumei; Gonzaga-Jauregui, Claudia; et al. (Brain, 2020)
MN1 encodes a transcriptional co-regulator without homology to other proteins, previously implicated in acute myeloid leukaemia and development of the palate. Large deletions encompassing MN1 have been reported in individuals with variable neurodevelopmental anomalies and non-specific facial features. We identified a cluster of de novo truncating mutations in MN1 in a cohort of 23 individuals with strikingly similar dysmorphic facial features, especially midface hypoplasia, and intellectual disability with severe expressive language delay. Imaging revealed an atypical form of rhombencephalosynapsis, a distinctive brain malformation characterized by partial or complete loss of the cerebellar vermis with fusion of the cerebellar hemispheres, in 8/10 individuals. Rhombencephalosynapsis has no previously known definitive genetic or environmental causes. Other frequent features included perisylvian polymicrogyria, abnormal posterior clinoid processes and persistent trigeminal artery. MN1 is encoded by only two exons. All mutations, including the recurrent variant p.Arg1295* observed in 8/21 probands, fall in the terminal exon or the extreme 3' region of exon 1, and are therefore predicted to result in escape from nonsense-mediated mRNA decay. This was confirmed in fibroblasts from three individuals. We propose that the condition described here, MN1 C-terminal truncation (MCTT) syndrome, is not due to MN1 haploinsufficiency but rather is the result of dominantly acting C-terminally truncated MN1 protein. Our data show that MN1 plays a critical role in human craniofacial and brain development, and opens the door to understanding the biological mechanisms underlying rhombencephalosynapsis.
Keywords: Abnormalities, Multiple; Adolescent; Basilar Artery; Carotid Arteries; Cerebellar Vermis; Cerebellum; Child; Child, Preschool; Cohort Studies; Comparative Genomic Hybridization; Craniofacial Abnormalities; Female; Fibroblasts; Humans; Imaging, Three-Dimensional; Infant; Intellectual Disability; Language Development Disorders; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Nervous System Malformations; Nonsense Mediated mRNA Decay; Polymicrogyria; Real-Time Polymerase Chain Reaction; RNA-Seq; Syndrome; Tomography, X-Ray Computed; Trans-Activators; Tumor Suppressor Proteins; Whole Exome Sequencing; Whole Genome Sequencing

Molecular diagnosis in recessive pediatric neurogenetic disease can help reduce disease recurrence in families. - Issa, Mahmoud Y; Chechlacz, Zinayida; Stanley, Valentina; George, Renee D; McEvoy-Venneri, Jennifer; Belandres, Denice; Elbendary, Hasnaa M; Gaber, Khaled R; Nabil, Ahmed; Abdel-Hamid, Mohamed S; Zaki, MAH S; Gleeson, Joseph G (BMC Med Genomics, 2020)
BACKGROUND: The causes for thousands of individually rare recessive diseases have been discovered since the adoption of next generation sequencing (NGS). Following the molecular diagnosis in older children in a family, parents could use this information to opt for fetal genotyping in subsequent pregnancies, which could inform decisions about elective termination of pregnancy. The use of NGS diagnostic sequencing in families has not been demonstrated to yield benefit in subsequent pregnancies to reduce recurrence. Here we evaluated whether genetic diagnosis in older children in families supports reduction in recurrence of recessive neurogenetic disease. METHODS: Retrospective study involving families with a child with a recessive pediatric brain disease (rPBD) that underwent NGS-based molecular diagnosis. Prenatal molecular testing was offered to couples in which a molecular diagnosis was made, to help couples seeking to prevent recurrence. With this information, families made decisions about elective termination. Pregnancies that were carried to term were assessed for the health of child and mother, and compared with historic recurrence risk of recessive disease. RESULTS: Between 2010 and 2016, 1172 families presented with a child a likely rPBD, 526 families received a molecular diagnosis, 91 families returned to the clinic with 101 subsequent pregnancies, and 84 opted for fetal genotyping. Sixty tested negative for recurrence for the biallelic mutation in the fetus, and all, except for one spontaneous abortion, carried to term, and were unaffected at follow-up. Of 24 that genotyped positive for the biallelic mutation, 16 were electively terminated, and 8 were carried to term and showed features of disease similar to that of the older affected sibling(s). Among the 101 pregnancies, disease recurrence in living offspring deviated from the expected 25% to the observed 12% ([95% CI 0·04 to 0·20], p = 0·011). CONCLUSIONS: Molecular diagnosis in an older child, coupled with prenatal fetal genotyping in subsequent pregnancies and genetic counselling, allows families to make informed decisions to reduce recessive neurogenetic disease recurrence.
Keywords: Child, Preschool; Female; Genes, Recessive; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genotype; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Male; Mutation; Nervous System Diseases; Pedigree; Pregnancy; Prenatal Diagnosis; Recurrence; Retrospective Studies

Monogenic variants in dystonia: an exome-wide sequencing study. - Zech, Michael; Jech, Robert; Boesch, Sylvia; Škorvánek, Matej; Weber, Sandrina; Wagner, Matias; Zhao, Chen; Jochim, Angela; Necpál, Ján; Dincer, Yasemin; Vill, Katharina; Distelmaier, Felix; et al. (Lancet Neurol, 2020)
BACKGROUND: Dystonia is a clinically and genetically heterogeneous condition that occurs in isolation (isolated dystonia), in combination with other movement disorders (combined dystonia), or in the context of multisymptomatic phenotypes (isolated or combined dystonia with other neurological involvement). However, our understanding of its aetiology is still incomplete. We aimed to elucidate the monogenic causes for the major clinical categories of dystonia. METHODS: For this exome-wide sequencing study, study participants were identified at 33 movement-disorder and neuropaediatric specialty centres in Austria, Czech Republic, France, Germany, Poland, Slovakia, and Switzerland. Each individual with dystonia was diagnosed in accordance with the dystonia consensus definition. Index cases were eligible for this study if they had no previous genetic diagnosis and no indication of an acquired cause of their illness. The second criterion was not applied to a subset of participants with a working clinical diagnosis of dystonic cerebral palsy. Genomic DNA was extracted from blood of participants and whole-exome sequenced. To find causative variants in known disorder-associated genes, all variants were filtered, and unreported variants were classified according to American College of Medical Genetics and Genomics guidelines. All considered variants were reviewed in expert round-table sessions to validate their clinical significance. Variants that survived filtering and interpretation procedures were defined as diagnostic variants. In the cases that went undiagnosed, candidate dystonia-causing genes were prioritised in a stepwise workflow. FINDINGS: We sequenced the exomes of 764 individuals with dystonia and 346 healthy parents who were recruited between June 1, 2015, and July 31, 2019. We identified causative or probable causative variants in 135 (19%) of 728 families, involving 78 distinct monogenic disorders. We observed a larger proportion of individuals with diagnostic variants in those with dystonia (either isolated or combined) with coexisting non-movement disorder-related neurological symptoms (100 [45%] of 222; excepting cases with evidence of perinatal brain injury) than in those with combined (19 [19%] of 98) or isolated (16 [4%] of 388) dystonia. Across all categories of dystonia, 104 (65%) of the 160 detected variants affected genes which are associated with neurodevelopmental disorders. We found diagnostic variants in 11 genes not previously linked to dystonia, and propose a predictive clinical score that could guide the implementation of exome sequencing in routine diagnostics. In cases without perinatal sentinel events, genomic alterations contributed substantively to the diagnosis of dystonic cerebral palsy. In 15 families, we delineated 12 candidate genes. These include IMPDH2, encoding a key purine biosynthetic enzyme, for which robust evidence existed for its involvement in a neurodevelopmental disorder with dystonia. We identified six variants in IMPDH2, collected from four independent cohorts, that were predicted to be deleterious de-novo variants and expected to result in deregulation of purine metabolism. INTERPRETATION: In this study, we have determined the role of monogenic variants across the range of dystonic disorders, providing guidance for the introduction of personalised care strategies and fostering follow-up pathophysiological explorations. FUNDING: Else Kröner-Fresenius-Stiftung, Technische Universität München, Helmholtz Zentrum München, Medizinische Universität Innsbruck, Charles University in Prague, Czech Ministry of Education, the Slovak Grant and Development Agency, the Slovak Research and Grant Agency.
Keywords: Adolescent; Child; Child, Preschool; Dystonia; Exome; Female; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Pedigree; Whole Exome Sequencing; Young Adult

Multi-omic studies on missense PLG variants in families with otitis media. - Bootpetch, Tori C; Hafrén, Lena; Elling, Christina L; Baschal, Erin E; Manichaikul, Ani W; Pine, Harold S; Szeremeta, Wasyl; Scholes, Melissa A; Cass, Stephen P; Larson, Eric D; Chan, Kenny H; Ishaq, Rafaqat; et al. (Sci Rep, 2020)
Otitis media (OM), a very common disease in young children, can result in hearing loss. In order to potentially replicate previously reported associations between OM and PLG, exome and Sanger sequencing, RNA-sequencing of saliva and middle ear samples, 16S rRNA sequencing, molecular modeling, and statistical analyses including transmission disequilibrium tests (TDT) were performed in a multi-ethnic cohort of 718 families and simplex cases with OM. We identified four rare PLG variants c.112A > G (p.Lys38Glu), c.782G > A (p.Arg261His), c.1481C > T (p.Ala494Val) and c.2045 T > A (p.Ile682Asn), and one common variant c.1414G > A (p.Asp472Asn). However TDT analyses for these PLG variants did not demonstrate association with OM in 314 families. Additionally PLG expression is very low or absent in normal or diseased middle ear in mouse and human, and salivary expression and microbial α-diversity were non-significant in c.1414G > A (p.Asp472Asn) carriers. Based on molecular modeling, the novel rare variants particularly c.782G > A (p.Arg261His) and c.2045 T > A (p.Ile682Asn) were predicted to affect protein structure. Exploration of other potential disease mechanisms will help elucidate how PLG contributes to OM susceptibility in humans. Our results underline the importance of following up findings from genome-wide association through replication studies, preferably using multi-omic datasets.
Keywords: Animals; Ear, Middle; Female; Genomics; Humans; Male; Mice; Microbiota; Mutation, Missense; Otitis Media; Pedigree; Plasminogen; Polymorphism, Single Nucleotide; Saliva

Multiplexed Functional Assessment of Genetic Variants in CARD11. - Meitlis, Iana; Allenspach, Eric J; Bauman, Bradly M; Phan, Isabelle Q; Dabbah, Gina; Schmitt, Erica G; Camp, Nathan D; Torgerson, Troy R; Nickerson, Deborah A; Bamshad, Michael J; Hagin, David; Luthers, Christopher R; et al. (Am J Hum Genet, 2020)
Genetic testing has increased the number of variants identified in disease genes, but the diagnostic utility is limited by lack of understanding variant function. CARD11 encodes an adaptor protein that expresses dominant-negative and gain-of-function variants associated with distinct immunodeficiencies. Here, we used a "cloning-free" saturation genome editing approach in a diploid cell line to simultaneously score 2,542 variants for decreased or increased function in the region of CARD11 associated with immunodeficiency. We also described an exon-skipping mechanism for CARD11 dominant-negative activity. The classification of reported clinical variants was sensitive (94.6%) and specific (88.9%), which rendered the data immediately useful for interpretation of seven coding and splicing variants implicated in immunodeficiency found in our clinic. This approach is generalizable for variant interpretation in many other clinically actionable genes, in any relevant cell type.
Keywords: Adenine; B-Cell CLL-Lymphoma 10 Protein; B-Lymphocytes; CARD Signaling Adaptor Proteins; Cell Line; Diploidy; Exons; Genes, Dominant; Genetic Variation; Guanylate Cyclase; Humans; Immunologic Deficiency Syndromes; Jurkat Cells; Lymphoma; NF-kappa B p50 Subunit; Piperidines; Polymorphism, Single Nucleotide; Primary Immunodeficiency Diseases; Sensitivity and Specificity

A mutation affecting laminin alpha 5 polymerisation gives rise to a syndromic developmental disorder. - Jones, Lynelle K; Lam, Rachel; McKee, Karen K; Aleksandrova, Maya; Dowling, John; Alexander, Stephen I; Mallawaarachchi, Amali; Cottle, Denny L; Short, Kieran M; Pais, Lynn; Miner, Jeffery H; Mallett, Andrew J; et al. (Development, 2020)
Laminin alpha 5 (LAMA5) is a member of a large family of proteins that trimerise and then polymerise to form a central component of all basement membranes. Consequently, the protein plays an instrumental role in shaping the normal development of the kidney, skin, neural tube, lung and limb, and many other organs and tissues. Pathogenic mutations in some laminins have been shown to cause a range of largely syndromic conditions affecting the competency of the basement membranes to which they contribute. We report the identification of a mutation in the polymerisation domain of LAMA5 in a patient with a complex syndromic disease characterised by defects in kidney, craniofacial and limb development, and by a range of other congenital defects. Using CRISPR-generated mouse models and biochemical assays, we demonstrate the pathogenicity of this variant, showing that the change results in a failure of the polymerisation of α/β/γ laminin trimers. Comparing these phenotypes with those apparent upon gene deletion in mice provides insights into the specific functional importance of laminin polymerisation during development and tissue homeostasis.
Keywords: Amino Acid Sequence; Animals; Animals, Newborn; Child, Preschool; Developmental Disabilities; Fetal Development; Fetus; Humans; Hydronephrosis; Infant, Newborn; Kidney; Laminin; Lung; Male; Mice; Mutation; Polymerization; Protein Domains; Syndrome

Mutation Distribution and Type Suggests Genetic Differences between the Etiology of Orofacial Clefting and Gastric Cancer. - Selvanathan, Arthavan; Nixon, Cheng Yee; Zhu, Ying; Scietti, Luigi; Forneris, Federico; Uribe, Lina M Moreno; Lidral, Andrew C; Jezewski, Peter A; Mulliken, John B; Murray, Jeffrey C; Buckley, Michael F; Cox, Timothy C; et al. (Genes (Basel), 2020)
Pathogenic variants in , encoding epithelial cadherin (E-cadherin), have been implicated in hereditary diffuse gastric cancer (HDGC), lobular breast cancer, and both syndromic and non-syndromic cleft lip/palate (CL/P). Despite the large number of mutations described, the nature of the phenotypic consequence of such mutations is currently not able to be predicted, creating significant challenges for genetic counselling. This study collates the phenotype and molecular data for available variants that have been classified, using the American College of Medical Genetics and Genomics criteria, as at least 'likely pathogenic', and correlates their molecular and structural characteristics to phenotype. We demonstrate that variant type and location differ between HDGC and CL/P, and that there is clustering of CL/P variants within linker regions between the extracellular domains of the cadherin protein. While these differences do not provide for exact prediction of the phenotype for a given mutation, they may contribute to more accurate assessments of risk for HDGC or CL/P for individuals with specific variants.
Keywords: Antigens, CD; Brain; Cadherins; Cleft Lip; Cleft Palate; Female; Genetic Counseling; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Male; Pedigree; Phenotype; Stomach Neoplasms

Mutation of CFAP57, a protein required for the asymmetric targeting of a subset of inner dynein arms in Chlamydomonas, causes primary ciliary dyskinesia. - Bustamante-Marin, Ximena M; Horani, Amjad; Stoyanova, Mihaela; Charng, Wu-Lin; Bottier, Mathieu; Sears, Patrick R; Yin, Wei-Ning; Daniels, Leigh Anne; Bowen, Hailey; Conrad, Donald F; Knowles, Michael R; Ostrowski, Lawrence E; et al. (PLoS Genet, 2020)
Primary ciliary dyskinesia (PCD) is characterized by chronic airway disease, reduced fertility, and randomization of the left/right body axis. It is caused by defects of motile cilia and sperm flagella. We screened a cohort of affected individuals that lack an obvious axonemal defect for pathogenic variants using whole exome capture, next generation sequencing, and bioinformatic analysis assuming an autosomal recessive trait. We identified one subject with an apparently homozygous nonsense variant [(c.1762C>T), p.(Arg588*)] in the uncharacterized CFAP57 gene. Interestingly, the variant results in the skipping of exon 11 (58 amino acids), which may be due to disruption of an exonic splicing enhancer. In normal human nasal epithelial cells, CFAP57 localizes throughout the ciliary axoneme. Nasal cells from the PCD patient express a shorter, mutant version of CFAP57 and the protein is not incorporated into the axoneme. The missing 58 amino acids include portions of WD repeats that may be important for loading onto the intraflagellar transport (IFT) complexes for transport or docking onto the axoneme. A reduced beat frequency and an alteration in ciliary waveform was observed. Knockdown of CFAP57 in human tracheobronchial epithelial cells (hTECs) recapitulates these findings. Phylogenetic analysis showed that CFAP57 is highly conserved in organisms that assemble motile cilia. CFAP57 is allelic with the BOP2/IDA8/FAP57 gene identified previously in Chlamydomonas reinhardtii. Two independent, insertional fap57 Chlamydomonas mutant strains show reduced swimming velocity and altered waveforms. Tandem mass tag (TMT) mass spectroscopy shows that FAP57 is missing, and the "g" inner dyneins (DHC7 and DHC3) and the "d" inner dynein (DHC2) are reduced, but the FAP57 paralog FBB7 is increased. Together, our data identify a homozygous variant in CFAP57 that causes PCD that is likely due to a defect in the inner dynein arm assembly process.
Keywords: 3T3 Cells; Adult; Animals; Axoneme; Cells, Cultured; Chlamydomonas reinhardtii; Cilia; Ciliary Motility Disorders; Codon, Nonsense; Conserved Sequence; Dyneins; Humans; Male; Mice; Microtubule-Associated Proteins; Plant Proteins; Proteins; Respiratory Mucosa

The mutational constraint spectrum quantified from variation in 141,456 humans. - Karczewski, Konrad J; Francioli, Laurent C; Tiao, Grace; Cummings, Beryl B; Alföldi, Jessica; Wang, Qingbo; Collins, Ryan L; Laricchia, Kristen M; Ganna, Andrea; Birnbaum, Daniel P; Gauthier, Laura D; Brand, Harrison; et al. (Nature, 2020)
Genetic variants that inactivate protein-coding genes are a powerful source of information about the phenotypic consequences of gene disruption: genes that are crucial for the function of an organism will be depleted of such variants in natural populations, whereas non-essential genes will tolerate their accumulation. However, predicted loss-of-function variants are enriched for annotation errors, and tend to be found at extremely low frequencies, so their analysis requires careful variant annotation and very large sample sizes. Here we describe the aggregation of 125,748 exomes and 15,708 genomes from human sequencing studies into the Genome Aggregation Database (gnomAD). We identify 443,769 high-confidence predicted loss-of-function variants in this cohort after filtering for artefacts caused by sequencing and annotation errors. Using an improved model of human mutation rates, we classify human protein-coding genes along a spectrum that represents tolerance to inactivation, validate this classification using data from model organisms and engineered human cells, and show that it can be used to improve the power of gene discovery for both common and rare diseases.
Keywords: Adult; Brain; Cardiovascular Diseases; Cohort Studies; Databases, Genetic; Exome; Female; Genes, Essential; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Loss of Function Mutation; Male; Mutation Rate; Proprotein Convertase 9; Reproducibility of Results; RNA, Messenger; Whole Exome Sequencing; Whole Genome Sequencing

Mutations disrupting neuritogenesis genes confer risk for cerebral palsy. - Jin, Sheng Chih; Lewis, Sara A; Bakhtiari, Somayeh; Zeng, Xue; Sierant, Michael C; Shetty, Sheetal; Nordlie, Sandra M; Elie, Aureliane; Corbett, Mark A; Norton, Bethany Y; van Eyk, Clare L; Haider, Shozeb; et al. (Nat Genet, 2020)
In addition to commonly associated environmental factors, genomic factors may cause cerebral palsy. We performed whole-exome sequencing of 250 parent-offspring trios, and observed enrichment of damaging de novo mutations in cerebral palsy cases. Eight genes had multiple damaging de novo mutations; of these, two (TUBA1A and CTNNB1) met genome-wide significance. We identified two novel monogenic etiologies, FBXO31 and RHOB, and showed that the RHOB mutation enhances active-state Rho effector binding while the FBXO31 mutation diminishes cyclin D levels. Candidate cerebral palsy risk genes overlapped with neurodevelopmental disorder genes. Network analyses identified enrichment of Rho GTPase, extracellular matrix, focal adhesion and cytoskeleton pathways. Cerebral palsy risk genes in enriched pathways were shown to regulate neuromotor function in a Drosophila reverse genetics screen. We estimate that 14% of cases could be attributed to an excess of damaging de novo or recessive variants. These findings provide evidence for genetically mediated dysregulation of early neuronal connectivity in cerebral palsy.
Keywords: Animals; beta Catenin; Cerebral Palsy; Cyclin D; Cytoskeleton; Drosophila; Exome; Extracellular Matrix; F-Box Proteins; Female; Focal Adhesions; Genetic Predisposition to Disease; Genome, Human; Humans; Male; Mutation; Neurites; rhoB GTP-Binding Protein; Risk Factors; Sequence Analysis, DNA; Signal Transduction; Tubulin; Tumor Suppressor Proteins; Whole Exome Sequencing

Mutations in ASPRV1 Cause Dominantly Inherited Ichthyosis. - Boyden, Lynn M; Zhou, Jing; Hu, Ronghua; Zaki, Theodore; Loring, Erin; Scott, Jared; Traupe, Heiko; Paller, Amy S; Lifton, Richard P; Choate, Keith A (Am J Hum Genet, 2020)
The discovery of genetic causes of inherited skin disorders has been pivotal to the understanding of epidermal differentiation, function, and renewal. Here we show via exome sequencing that mutations in ASPRV1 (aspartic peptidase retroviral-like 1) cause a dominant Mendelian disorder featuring palmoplantar keratoderma and lamellar ichthyosis, a phenotype that has otherwise been exclusively recessive. ASPRV1 encodes a mammalian-specific and stratified epithelia-specific protease important in processing of filaggrin, a critical component of the uppermost epidermal layer. Three different heterozygous ASPRV1 missense mutations in four unrelated ichthyosis kindreds segregate with disease and disrupt protein residues within close proximity to each other and autocatalytic cleavage sites. Expression of mutant ASPRV1 proteins demonstrates that all three mutations alter ASPRV1 auto-cleavage and filaggrin processing, a function vital to epidermal barrier integrity.
Keywords: Aspartic Acid Endopeptidases; Heredity; Heterozygote; Humans; Ichthyosis, Lamellar; Intermediate Filament Proteins; Mutation, Missense; Phenotype; Skin Diseases; Whole Exome Sequencing

Mutations in GET4 disrupt the transmembrane domain recognition complex pathway. - Tambe, Mitali A; Ng, Bobby G; Shimada, Shino; Wolfe, Lynne A; Adams, David R; Gahl, William A; Bamshad, Michael J; Nickerson, Deborah A; Malicdan, May C V; Freeze, Hudson H (J Inherit Metab Dis, 2020)
The transmembrane domain recognition complex (TRC) targets cytoplasmic C-terminal tail-anchored (TA) proteins to their respective membranes in the endoplasmic reticulum (ER), Golgi, and mitochondria. It is composed of three proteins, GET4, BAG6, and GET5. We identified an individual with compound heterozygous missense variants (p.Arg122His, p.Ile279Met) in GET4 that reduced all three TRC proteins by 70% to 90% in his fibroblasts, suggesting a possible defect in TA protein targeting. He presented with global developmental delay, intellectual disabilities, seizures, facial dysmorphism, and delayed bone age. We found the TA protein, syntaxin 5, is poorly targeted to Golgi membranes compared to normal controls. Since GET4 regulates ER to Golgi transport, we hypothesized that such transport would be disrupted in his fibroblasts, and discovered that retrograde (but not anterograde) transport was significantly reduced. Despite reduction in the three TRC proteins, their mRNA levels were unchanged, suggesting increased degradation in patient fibroblasts. Treating fibroblasts with the FDA-approved proteasome inhibitor, bortezomib (10 nM), restored syntaxin 5 localization and nearly normalized the levels of all three TRC proteins. Our study identifies the first individual with GET4 mutations.

Mutations in GRK2 cause Jeune syndrome by impairing Hedgehog and canonical Wnt signaling. - Bosakova, Michaela; AbrAHm, Sara P; Nita, Alexandru; Hruba, Eva; Buchtova, Marcela; Taylor, S Paige; Duran, Ivan; Martin, Jorge; Svozilova, Katerina; Barta, Tomas; Varecha, Miroslav; Balek, Lukas; et al. (EMBO Mol Med, 2020)
Mutations in genes affecting primary cilia cause ciliopathies, a diverse group of disorders often affecting skeletal development. This includes Jeune syndrome or asphyxiating thoracic dystrophy (ATD), an autosomal recessive skeletal disorder. Unraveling the responsible molecular pathology helps illuminate mechanisms responsible for functional primary cilia. We identified two families with ATD caused by loss-of-function mutations in the gene encoding adrenergic receptor kinase 1 (ADRBK1 or GRK2). GRK2 cells from an affected individual homozygous for the p.R158* mutation resulted in loss of GRK2, and disrupted chondrocyte growth and differentiation in the cartilage growth plate. GRK2 null cells displayed normal cilia morphology, yet loss of GRK2 compromised cilia-based signaling of Hedgehog (Hh) pathway. Canonical Wnt signaling was also impaired, manifested as a failure to respond to Wnt ligand due to impaired phosphorylation of the Wnt co-receptor LRP6. We have identified GRK2 as an essential regulator of skeletogenesis and demonstrate how both Hh and Wnt signaling mechanistically contribute to skeletal ciliopathies.

Mutations in KRT10 in epidermolytic acanthoma. - Cheraghlou, Shayan; Atzmony, Lihi; Roy, Simon F; McNiff, Jennifer M; Choate, Keith A (J Cutan Pathol, 2020)
BACKGROUND: Epidermolytic acanthoma (EA) is a rare acquired lesion demonstrating a characteristic histopathological pattern of epidermal degeneration referred to as epidermolytic hyperkeratosis (EHK). On histopathological analysis, EA appears nearly identical to inherited EHK-associated dermatoses such as epidermolytic ichthyosis and ichthyosis bullosa of Siemens. While it has been speculated that EA is caused by mutations in KRT10, KRT1, or KRT2 found in these inherited dermatoses, none have yet been identified. Herein, we aim to identify the contributions of keratin mutations to EA. METHODS: Using genomic DNA extracted from paraffin-embedded samples from departmental archives, we evaluated a discovery cohort using whole-exome sequencing (WES) and assessed remaining samples using Sanger sequencing screening and restriction fragment length polymorphism (RFLP) analysis. RESULTS: DNA from 16/20 cases in our sample was of sufficient quality for polymerase chain reaction amplification. WES of genomic DNA from lesional tissue revealed KRT10 c.466C > T, p.Arg156Cys mutations in 2/3 samples submitted for examination. RFLP analysis of these samples as well as eight additional samples confirmed the mutations identified via WES and identified four additional cases with Arg156 mutations. In sum, 6/11 screened cases showed hotspot mutation in KRT10. CONCLUSIONS: Hotspot mutations in the Arg156 position of KRT10, known to cause epidermolytic ichthyosis, also underlie EA.
Keywords: Acanthoma; Adult; Aged; Aged, 80 and over; Female; Genomics; Humans; Hyperkeratosis, Epidermolytic; Ichthyosis Bullosa of Siemens; Keratin-10; Keratins; Male; Middle Aged; Mutation; Skin Neoplasms; Whole Exome Sequencing

Mutations in MYLPF Cause a Novel Segmental Amyoplasia that Manifests as Distal Arthrogryposis. - Chong, Jessica X; Talbot, Jared C; Teets, Emily M; Previs, Samantha; Martin, Brit L; Shively, Kathryn M; Marvin, Colby T; Aylsworth, Arthur S; Saadeh-Haddad, Reem; Schatz, Ulrich A; Inzana, Francesca; Ben-Omran, Tawfeg; et al. (Am J Hum Genet, 2020)
We identified ten persons in six consanguineous families with distal arthrogryposis (DA) who had congenital contractures, scoliosis, and short stature. Exome sequencing revealed that each affected person was homozygous for one of two different rare variants (c.470G>T [p.Cys157Phe] or c.469T>C [p.Cys157Arg]) affecting the same residue of myosin light chain, phosphorylatable, fast skeletal muscle (MYLPF). In a seventh family, a c.487G>A (p.Gly163Ser) variant in MYLPF arose de novo in a father, who transmitted it to his son. In an eighth family comprised of seven individuals with dominantly inherited DA, a c.98C>T (p.Ala33Val) variant segregated in all four persons tested. Variants in MYLPF underlie both dominant and recessively inherited DA. Mylpf protein models suggest that the residues associated with dominant DA interact with myosin whereas the residues altered in families with recessive DA only indirectly impair this interaction. Pathological and histological exam of a foot amputated from an affected child revealed complete absence of skeletal muscle (i.e., segmental amyoplasia). To investigate the mechanism for this finding, we generated an animal model for partial MYLPF impairment by knocking out zebrafish mylpfa. The mylpfa mutant had reduced trunk contractile force and complete pectoral fin paralysis, demonstrating that mylpf impairment most severely affects limb movement. mylpfa mutant muscle weakness was most pronounced in an appendicular muscle and was explained by reduced myosin activity and fiber degeneration. Collectively, our findings demonstrate that partial loss of MYLPF function can lead to congenital contractures, likely as a result of degeneration of skeletal muscle in the distal limb.
Keywords: Adolescent; Amino Acid Sequence; Animals; Arthrogryposis; Child; Contracture; Extremities; Female; Humans; Male; Muscle, Skeletal; Musculoskeletal Abnormalities; Mutation; Myosin Light Chains; Myosins; Pedigree; Young Adult; Zebrafish

Mutations of the Transcriptional Corepressor ZMYM2 Cause Syndromic Urinary Tract Malformations. - Connaughton, Dervla M; Dai, Rufeng; Owen, Danielle J; Marquez, Jonathan; Mann, Nina; GrAHm-Paquin, Adda L; Nakayama, Makiko; Coyaud, Etienne; Laurent, Estelle M N; St-Germain, Jonathan R; Blok, Lot Snijders; Vino, Arianna; et al. (Am J Hum Genet, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUT) constitute one of the most frequent birth defects and represent the most common cause of chronic kidney disease in the first three decades of life. Despite the discovery of dozens of monogenic causes of CAKUT, most pathogenic pathways remain elusive. We performed whole-exome sequencing (WES) in 551 individuals with CAKUT and identified a heterozygous de novo stop-gain variant in ZMYM2 in two different families with CAKUT. Through collaboration, we identified in total 14 different heterozygous loss-of-function mutations in ZMYM2 in 15 unrelated families. Most mutations occurred de novo, indicating possible interference with reproductive function. Human disease features are replicated in X. tropicalis larvae with morpholino knockdowns, in which expression of truncated ZMYM2 proteins, based on individual mutations, failed to rescue renal and craniofacial defects. Moreover, heterozygous Zmym2-deficient mice recapitulated features of CAKUT with high penetrance. The ZMYM2 protein is a component of a transcriptional corepressor complex recently linked to the silencing of developmentally regulated endogenous retrovirus elements. Using protein-protein interaction assays, we show that ZMYM2 interacts with additional epigenetic silencing complexes, as well as confirming that it binds to FOXP1, a transcription factor that has also been linked to CAKUT. In summary, our findings establish that loss-of-function mutations of ZMYM2, and potentially that of other proteins in its interactome, as causes of human CAKUT, offering new routes for studying the pathogenesis of the disorder.
Keywords: Amphibian Proteins; Animals; Case-Control Studies; Child; Child, Preschool; DNA-Binding Proteins; Epigenesis, Genetic; Family; Female; Forkhead Transcription Factors; Heterozygote; Humans; Infant; Larva; Male; Mice; Mice, Knockout; Morpholinos; Mutation; Pedigree; Protein Binding; Repressor Proteins; Transcription Factors; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing; Xenopus

Natural history of Ollier disease and Maffucci syndrome: Patient survey and review of clinical literature. - El Abiad, Jad M; Robbins, Sarah M; Cohen, Bernard; Levin, Adam S; Valle, David L; Morris, Carol D; de Macena Sobreira, Nara L (Am J Med Genet A, 2020)
Ollier disease (OD) and Maffucci syndrome (MS) are characterized by multiple enchondromas. Patients with MS also have benign vascular overgrowths that become malignant in 8.5% of cases. OD is characterized by multiple enchondromas, typically unilateral in distribution with a predilection for the appendicular skeleton. MS is characterized by multiple enchondromas bilaterally distributed in most of the cases. Both disorders feature multiple swellings on the extremity, deformity around the joints, limitations in joint mobility, scoliosis, bone shortening, leg-length discrepancy, gait disturbances, pain, loss of function, and pathological fractures. About 50% of patients with OD or MS develop a malignancy, such as chondrosarcoma, glioma, and ovarian juvenile granulosa cell tumor. To better understand the natural history of OD and MS, we reviewed 287 papers describing patients with OD and MS. We also created a survey that was distributed directly to 162 patients through Facebook. Here, we compare the review of the cases described in the literature to the survey's responses. The review of the literature showed that: the patients with OD are diagnosed at a younger age; the prevalence of chondrosarcomas among patients with OD or MS was ~30%; in four patients, vascular anomalies were identified in internal organs only; and, the prevalence of cancer among patients with OD or MS was ~50%. With these data, health care providers will better understand the natural history, severity, and prognosis of these diseases and the prevalence of malignancies in these patients. Here, we recommend new guidelines for the care of patients with OD and MS.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chondrosarcoma; Enchondromatosis; Female; Granulosa Cell Tumor; Humans; Infant; Infant, Newborn; Male; Middle Aged; Ovarian Neoplasms; Prognosis; Young Adult

NEMF mutations that impair ribosome-associated quality control are associated with neuromuscular disease. - Martin, Paige B; Kigoshi-Tansho, Yu; Sher, Roger B; Ravenscroft, Gianina; Stauffer, Jennifer E; Kumar, Rajesh; Yonashiro, Ryo; Müller, Tina; Griffith, Christopher; Allen, William; Pehlivan, Davut; Harel, Tamar; et al. (Nat Commun, 2020)
A hallmark of neurodegeneration is defective protein quality control. The E3 ligase Listerin (LTN1/Ltn1) acts in a specialized protein quality control pathway-Ribosome-associated Quality Control (RQC)-by mediating proteolytic targeting of incomplete polypeptides produced by ribosome stalling, and Ltn1 mutation leads to neurodegeneration in mice. Whether neurodegeneration results from defective RQC and whether defective RQC contributes to human disease have remained unknown. Here we show that three independently-generated mouse models with mutations in a different component of the RQC complex, NEMF/Rqc2, develop progressive motor neuron degeneration. Equivalent mutations in yeast Rqc2 selectively interfere with its ability to modify aberrant translation products with C-terminal tails which assist with RQC-mediated protein degradation, suggesting a pathomechanism. Finally, we identify NEMF mutations expected to interfere with function in patients from seven families presenting juvenile neuromuscular disease. These uncover NEMF's role in translational homeostasis in the nervous system and implicate RQC dysfunction in causing neurodegeneration.
Keywords: Amino Acid Sequence; Animals; Female; Humans; Male; Mice; Mice, Knockout; Mutation; Neuromuscular Diseases; Proteolysis; Ribosomes; RNA-Binding Proteins; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins; Sequence Alignment

Neurophysiological and Genetic Findings in Patients With Juvenile Myoclonic Epilepsy. - Stefani, Stefani; Kousiappa, Ioanna; Nicolaou, Nicoletta; Papathanasiou, Eleftherios S; Oulas, Anastasis; Fanis, Pavlos; Neocleous, Vassos; Phylactou, Leonidas A; Spyrou, George M; Papacostas, Savvas S (Front Integr Neurosci, 2020)
Objective: Transcranial magnetic stimulation (TMS), a non-invasive procedure, stimulates the cortex evaluating the central motor pathways. The response is called motor evoked potential (MEP). Polyphasia results when the response crosses the baseline more than twice (zero crossing). Recent research shows MEP polyphasia in patients with generalized genetic epilepsy (GGE) and their first-degree relatives compared with controls. Juvenile Myoclonic Epilepsy (JME), a GGE type, is not well studied regarding polyphasia. In our study, we assessed polyphasia appearance probability with TMS in JME patients, their healthy first-degree relatives and controls. Two genetic approaches were applied to uncover genetic association with polyphasia. Methods: 20 JME patients, 23 first-degree relatives and 30 controls underwent TMS, obtaining 10-15 MEPs per participant. We evaluated MEP mean number of phases, proportion of MEP trials displaying polyphasia for each subject and variability between groups. Participants underwent whole exome sequencing (WES) via trio-based analysis and two-case scenario. Extensive bioinformatics analysis was applied. Results: We identified increased polyphasia in patients (85%) and relatives (70%) compared to controls (47%) and significantly higher mean number of zero crossings (i.e., occurrence of phases) (patients 1.49, relatives 1.46, controls 1.22; < 0.05). Trio-based analysis revealed a candidate polymorphism, p.Glu270del,in , in JME patients and their relatives presenting polyphasia. Sanger sequencing analysis in remaining participants showed no significant association. In two-case scenario, a machine learning approach was applied in variants identified from odds ratio analysis and risk prediction scores were obtained for polyphasia. The results revealed 61 variants of which none was associated with polyphasia. Risk prediction scores indeed showed lower probability for non-polyphasic subjects on having polyphasia and higher probability for polyphasic subjects on having polyphasia. Conclusion: Polyphasia was present in JME patients and relatives in contrast to controls. Although no known clinical symptoms are linked to polyphasia this neurophysiological phenomenon is likely due to common cerebral electrophysiological abnormality. We did not discover direct association between genetic variants obtained and polyphasia. It is likely these genetic traits alone cannot provoke polyphasia, however, this predisposition combined with disturbed brain-electrical activity and tendency to generate seizures may increase the risk of developing polyphasia, mainly in patients and relatives.

New drugs on the horizon for cerebral edema: what's in the clinical development pipeline? - Robert, Stephanie M; Reeves, Benjamin C; Alper, Seth L; Zhang, Jinwei; Kahle, Kristopher T (Expert Opin Investig Drugs, 2020)
INTRODUCTION: Research has advanced our understanding of the molecular and cellular mechanisms of cerebral edema and has propelled the development of novel antiedema therapeutics. Current evidence supports aberrant neuro-glial ion transport as a central mechanism that underlies pathological fluid accumulation after central nervous system injury. AREAS COVERED: Novel agents in clinical development show potential in altering the natural history and treatment of cerebral edema. Using the PubMed and Google Scholar databases, we review recent advances in our understanding of cerebral edema and describe agents under active investigation, their mechanism, and their application in recent and ongoing clinical trials. EXPERT OPINION: Pharmacotherapies that target molecular mechanisms underlying the compensatory post-injury response of ion channels and transporters that lead to pathological alteration of osmotic gradients are the most promising therapeutic strategies. Repurposing of drugs such as glyburide that inhibit the aberrant upregulation of ion channels such as SUR1-TRPM4, and novel agents, such as ZT-1a, which reestablish physiological regulation of ion channels such as NKCC1/KCC, could be useful adjuvants to prevent and even reverse fluid accumulation in the brain parenchyma.
Keywords: Animals; Brain Edema; Drug Development; Drug Repositioning; Drugs, Investigational; Humans; Molecular Targeted Therapy

Next Generation Sequencing of 134 Children with Autism Spectrum Disorder and Regression. - Yin, Jiani; Chun, Chun-An; Zavadenko, Nikolay N; Pechatnikova, Natalia L; Naumova, Oxana Yu; Doddapaneni, Harsha V; Hu, Jianhong; Muzny, Donna M; Schaaf, Christian P; Grigorenko, Elena L (Genes (Basel), 2020)
Approximately 30% of individuals with autism spectrum disorder (ASD) experience developmental regression, the etiology of which remains largely unknown. We performed a complete literature search and identified 47 genes that had been implicated in such cases. We sequenced these genes in a preselected cohort of 134 individuals with regressive autism. In total, 16 variants in 12 genes with evidence supportive of pathogenicity were identified. They were classified as variants of uncertain significance based on ACMG standards and guidelines. Among these were recurring variants in and , variants in genes that were linked to syndromic forms of ASD (, , , , , and ), and variants in the form of oligogenic heterozygosity (, , and ).
Keywords: Autism Spectrum Disorder; Child; Child, Preschool; Cohort Studies; Disease Progression; Female; Gene Expression Regulation; Genetic Markers; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Infant; Male; Mutation

Non-parametric Polygenic Risk Prediction via Partitioned GWAS Summary Statistics. - Chun, Sung; Imakaev, Maxim; Hui, Daniel; Patsopoulos, Nikolaos A; Neale, Benjamin M; Kathiresan, Sekar; Stitziel, Nathan O; Sunyaev, Shamil R (Am J Hum Genet, 2020)
In complex trait genetics, the ability to predict phenotype from genotype is the ultimate measure of our understanding of genetic architecture underlying the heritability of a trait. A complete understanding of the genetic basis of a trait should allow for predictive methods with accuracies approaching the trait's heritability. The highly polygenic nature of quantitative traits and most common phenotypes has motivated the development of statistical strategies focused on combining myriad individually non-significant genetic effects. Now that predictive accuracies are improving, there is a growing interest in the practical utility of such methods for predicting risk of common diseases responsive to early therapeutic intervention. However, existing methods require individual-level genotypes or depend on accurately specifying the genetic architecture underlying each disease to be predicted. Here, we propose a polygenic risk prediction method that does not require explicitly modeling any underlying genetic architecture. We start with summary statistics in the form of SNP effect sizes from a large GWAS cohort. We then remove the correlation structure across summary statistics arising due to linkage disequilibrium and apply a piecewise linear interpolation on conditional mean effects. In both simulated and real datasets, this new non-parametric shrinkage (NPS) method can reliably allow for linkage disequilibrium in summary statistics of 5 million dense genome-wide markers and consistently improves prediction accuracy. We show that NPS improves the identification of groups at high risk for breast cancer, type 2 diabetes, inflammatory bowel disease, and coronary heart disease, all of which have available early intervention or prevention treatments.
Keywords: Aged; Cohort Studies; Diabetes Mellitus, Type 2; Female; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Middle Aged; Models, Genetic; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Novel congenital disorder of O-linked glycosylation caused by GALNT2 loss of function. - Zilmer, Monica; Edmondson, Andrew C; Khetarpal, Sumeet A; Alesi, Viola; Zaki, MAH S; Rostasy, Kevin; Madsen, Camilla G; Lepri, Francesca R; Sinibaldi, Lorenzo; Cusmai, Raffaella; Novelli, Antonio; Issa, Mahmoud Y; et al. (Brain, 2020)
Congenital disorders of glycosylation are a growing group of rare genetic disorders caused by deficient protein and lipid glycosylation. Here, we report the clinical, biochemical, and molecular features of seven patients from four families with GALNT2-congenital disorder of glycosylation (GALNT2-CDG), an O-linked glycosylation disorder. GALNT2 encodes the Golgi-localized polypeptide N-acetyl-d-galactosamine-transferase 2 isoenzyme. GALNT2 is widely expressed in most cell types and directs initiation of mucin-type protein O-glycosylation. All patients showed loss of O-glycosylation of apolipoprotein C-III, a non-redundant substrate for GALNT2. Patients with GALNT2-CDG generally exhibit a syndrome characterized by global developmental delay, intellectual disability with language deficit, autistic features, behavioural abnormalities, epilepsy, chronic insomnia, white matter changes on brain MRI, dysmorphic features, decreased stature, and decreased high density lipoprotein cholesterol levels. Rodent (mouse and rat) models of GALNT2-CDG recapitulated much of the human phenotype, including poor growth and neurodevelopmental abnormalities. In behavioural studies, GALNT2-CDG mice demonstrated cerebellar motor deficits, decreased sociability, and impaired sensory integration and processing. The multisystem nature of phenotypes in patients and rodent models of GALNT2-CDG suggest that there are multiple non-redundant protein substrates of GALNT2 in various tissues, including brain, which are critical to normal growth and development.
Keywords: Adolescent; Animals; Apolipoprotein C-III; Child; Child, Preschool; Developmental Disabilities; Female; Glycosylation; Humans; Loss of Function Mutation; Male; Mice; N-Acetylgalactosaminyltransferases; Pedigree; Rats; Young Adult

A novel homozygous KY variant causing a complex neurological disorder. - Arif, Beenish; Rasheed, Arisha; Kumar, Kishore R; Fatima, Amara; Abbas, Ghazanfar; Wohler, Elizabeth; Sobriera, Nara; Lohmann, Katja; Naz, Sadaf (Eur J Med Genet, 2020)
Mutations in the gene kyphoscoliosis peptidase (KY) are known to cause myofibrillar myopathy-7 and hereditary spastic paraplegia. We investigated the genetic cause of a complex neurological phenotype in a consanguineous Pakistani family with four affected members, manifesting lower limb spasticity and weakness, toe walking, pes equinovarus, and a speech disorder. Genome-wide linkage analysis with microsatellite markers delineated chromosome 3q22.2-q24 harboring the disease gene. Whole exome sequencing was performed for two subjects, identifying a homozygous 14-bp frameshift deletion NM_178554.6:c.842_855del; p(Val281GlyfsTer18) in KY. The variant segregated with the phenotype and was absent from public databases and 100 ethnically matched controls. We confirm a novel homozygous KY variant causing a complex neurological phenotype in this family. A review of previously reported KY variants suggests that variants in this gene can cause a spectrum of neurological phenotypes.
Keywords: Child; Female; Frameshift Mutation; Gait; Homozygote; Humans; Male; Myopathies, Structural, Congenital; Pedigree; Peptide Hydrolases; Phenotype; Spastic Paraplegia, Hereditary; Speech

A novel homozygous variant in results in a neurodevelopmental disorder and disrupts TRAPP complex function. - Al-Deri, Noraldin; Okur, Volkan; Ahimaz, Priyanka; Milev, Miroslav; Valivullah, Zaheer; Hagen, Jacob; Sheng, Yufeng; Chung, Wendy; Sacher, Michael; Ganapathi, Mythily (J Med Genet, 2020)
BACKGROUND: Next-generation sequencing has facilitated the diagnosis of neurodevelopmental disorders with variable and non-specific clinical findings. Recently, a homozygous missense p.(Asp37Tyr) variant in a core subunit of TRAPP complexes which function as tethering factors during membrane trafficking, was reported in two unrelated individuals with neurodevelopmental delay, post-infectious encephalopathy-associated developmental arrest, tetraplegia and accompanying rhabdomyolysis. METHODS: We performed whole genome sequencing on members of an Ashkenazi Jewish pedigree to identify the underlying genetic aetiology of global developmental delay/intellectual disability in three affected siblings. To assess the effect of the identified variant, we performed biochemical and cell biological functional studies on the TRAPPC2L protein. RESULTS: A rare homozygous predicted deleterious missense variant, p.(Ala2Gly), in was identified in the affected siblings and it segregated with the neurodevelopmental phenotype within the family. Using a yeast two-hybrid assay and binding, we demonstrate that the p.(Ala2Gly) variant, but not the p.(Asp37Tyr) variant, disrupted the interaction between TRAPPC2L and another core TRAPP protein, TRAPPC6a. Size exclusion chromatography suggested that this variant affects the assembly of TRAPP complexes. Employing two different membrane trafficking assays using fibroblasts from one of the affected siblings, we found a delay in traffic into and out of the Golgi. Similar to the p.(Asp37Tyr) variant, the p.(Ala2Gly) variant resulted in an increase in the levels of active RAB11. CONCLUSION: Our data fill in a gap in the knowledge of TRAPP architecture with TRAPPC2L interacting with TRAPPC6a, positioning it as a putative adaptor for other TRAPP subunits. Collectively, our findings support the pathogenicity of the p.(Ala2Gly) variant.

Novel pathogenic genomic variants leading to autosomal dominant and recessive Robinow syndrome. - Zhang, Chaofan; Mazzeu, Juliana F; Eisfeldt, Jesper; Grochowski, Christopher M; White, Janson; Akdemir, Zeynep C; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Lindstrand, Anna; Lupski, James R; Sutton, V Reid; et al. (Am J Med Genet A, 2020)
Robinow syndrome (RS) is a genetically heterogeneous disorder characterized by skeletal dysplasia and a distinctive facial appearance. Previous studies have revealed locus heterogeneity with rare variants in DVL1, DVL3, FZD2, NXN, ROR2, and WNT5A underlying the etiology of RS. The aforementioned "Robinow-associated genes" and their gene products all play a role in the WNT/planar cell polarity signaling pathway. We performed gene-targeted Sanger sequencing, exome sequencing, genome sequencing, and array comparative genomic hybridization on four subjects with a clinical diagnosis of RS who had not had prior DNA testing. Individuals in our cohort were found to carry pathogenic or likely pathogenic variants in three RS related genes: DVL1, ROR2, and NXN. One subject was found to have a nonsense variant (c.817C > T [p.Gln273*]) in NXN in trans with an ~1 Mb telomeric deletion on chromosome 17p containing NXN, which supports our contention that biallelic NXN variant alleles are responsible for a novel autosomal recessive RS locus. These findings provide increased understanding of the role of WNT signaling in skeletal development and maintenance. These data further support the hypothesis that dysregulation of the noncanonical WNT pathway in humans gives rise to RS.

A novel RFC1 repeat motif (ACAGG) in two Asia-Pacific CANVAS families. - Scriba, Carolin K; Beecroft, Sarah J; Clayton, Joshua S; Cortese, Andrea; Sullivan, Roisin; Yau, Wai Yan; Dominik, Natalia; Rodrigues, Miriam; Walker, Elizabeth; Dyer, Zoe; Wu, Teddy Y; Davis, Mark R; et al. (Brain, 2020)
Cerebellar ataxia, neuropathy and vestibular areflexia syndrome (CANVAS) is a progressive late-onset, neurological disease. Recently, a pentanucleotide expansion in intron 2 of RFC1 was identified as the genetic cause of CANVAS. We screened an Asian-Pacific cohort for CANVAS and identified a novel RFC1 repeat expansion motif, (ACAGG)exp, in three affected individuals. This motif was associated with additional clinical features including fasciculations and elevated serum creatine kinase. These features have not previously been described in individuals with genetically-confirmed CANVAS. Haplotype analysis showed our patients shared the same core haplotype as previously published, supporting the possibility of a single origin of the RFC1 disease allele. We analysed data from >26 000 genetically diverse individuals in gnomAD to show enrichment of (ACAGG) in non-European populations.
Keywords: Aged; Asian Continental Ancestry Group; Bilateral Vestibulopathy; Cerebellar Ataxia; Cohort Studies; DNA Repeat Expansion; Female; Humans; Indonesia; Male; Middle Aged; Pedigree; Replication Protein C

Organic Solute Transporter Alpha Deficiency: A Disorder With Cholestasis, Liver Fibrosis, and Congenital Diarrhea. - Gao, Emily; Cheema, Huma; Waheed, Nadia; Mushtaq, Iqra; Erden, Nihan; Nelson-Williams, Carol; Jain, Dhanpat; Soroka, Carol J; Boyer, James L; Khalil, Youssef; Clayton, Peter T; Mistry, Pramod K; et al. (Hepatology, 2020)
Keywords: Child, Preschool; Cholestasis; Diarrhea; Humans; Liver; Liver Cirrhosis; Male; Mutation; Pedigree; Receptors, G-Protein-Coupled

Otitis media susceptibility and shifts in the head and neck microbiome due to variants. - Frank, Daniel N; Giese, Arnaud P J; Hafrén, Lena; Bootpetch, Tori C; Yarza, Talitha Karisse L; Steritz, Matthew J; Pedro, Melquiadesa; Labra, Patrick John; Daly, Kathleen A; Tantoco, Ma Leah C; Szeremeta, Wasyl; Reyes-Quintos, Maria Rina T; et al. (J Med Genet, 2020)
BACKGROUND: Otitis media (OM) susceptibility has significant heritability; however, the role of rare variants in OM is mostly unknown. Our goal is to identify novel rare variants that confer OM susceptibility. METHODS: We performed exome and Sanger sequencing of >1000 DNA samples from 551 multiethnic families with OM and unrelated individuals, RNA-sequencing and microbiome sequencing and analyses of swabs from the outer ear, middle ear, nasopharynx and oral cavity. We also examined protein localisation and gene expression in infected and healthy middle ear tissues. RESULTS: A large, intermarried pedigree that includes 81 OM-affected and 53 unaffected individuals cosegregates two known rare variants, a common variant and a rare, novel pathogenic variant c.1682A>G (p.Glu561Gly) within (LOD=4.09). Carriage of the missense variant resulted in increased relative abundance of Microbacteriaceae in the middle ear, along with occurrence of Microbacteriaceae in the outer ear and oral cavity but not the nasopharynx. Eight additional novel variants were identified in 12 families and individuals with OM. A role for in OM susceptibility is further supported by lower RNA counts in variant carriers, strong SPINK5 localisation in outer ear skin, faint localisation to middle ear mucosa and eardrum and increased expression in human cholesteatoma. CONCLUSION: variants confer susceptibility to non-syndromic OM. These variants potentially contribute to middle ear pathology through breakdown of mucosal and epithelial barriers, immunodeficiency such as poor vaccination response, alteration of head and neck microbiota and facilitation of entry of opportunistic pathogens into the middle ear.

The Parkinson's Disease Genome-Wide Association Study Locus Browser. - Grenn, Francis P; Kim, Jonggeol J; Makarious, Mary B; Iwaki, Hirotaka; Illarionova, Anastasia; Brolin, Kajsa; Kluss, Jillian H; Schumacher-Schuh, Artur F; Leonard, Hampton; Faghri, Faraz; Billingsley, Kimberley; Krohn, Lynne; et al. (Mov Disord, 2020)
BACKGROUND: Parkinson's disease (PD) is a neurodegenerative disease with an often complex component identifiable by genome-wide association studies. The most recent large-scale PD genome-wide association studies have identified more than 90 independent risk variants for PD risk and progression across more than 80 genomic regions. One major challenge in current genomics is the identification of the causal gene(s) and variant(s) at each genome-wide association study locus. The objective of the current study was to create a tool that would display data for relevant PD risk loci and provide guidance with the prioritization of causal genes and potential mechanisms at each locus. METHODS: We included all significant genome-wide signals from multiple recent PD genome-wide association studies including themost recent PD risk genome-wide association study, age-at-onset genome-wide association study, progression genome-wide association study, and Asian population PD risk genome-wide association study. We gathered data for all genes 1 Mb up and downstream of each variant to allow users to assess which gene(s) are most associated with the variant of interest based on a set of self-ranked criteria. Multiple databases were queried for each gene to collect additional causal data. RESULTS: We created a PD genome-wide association study browser tool (https://pdgenetics.shinyapps.io/GWASBrowser/) to assist the PD research community with the prioritization of genes for follow-up functional studies to identify potential therapeutic targets. CONCLUSIONS: Our PD genome-wide association study browser tool provides users with a useful method of identifying potential causal genes at all known PD risk loci from large-scale PD genome-wide association studies. We plan to update this tool with new relevant data as sample sizes increase and new PD risk loci are discovered. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society. This article has been contributed to by US Government employees and their work is in the public domain in the USA.
Keywords: Age of Onset; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Neurodegenerative Diseases; Parkinson Disease; Risk Factors

Parliament2: Accurate structural variant calling at scale. - Zarate, Samantha; Carroll, Andrew; Mahmoud, Medhat; Krasheninina, Olga; Jun, Goo; Salerno, William J; Schatz, Michael C; Boerwinkle, Eric; Gibbs, Richard A; Sedlazeck, Fritz J (Gigascience, 2020)
BACKGROUND: Structural variants (SVs) are critical contributors to genetic diversity and genomic disease. To predict the phenotypic impact of SVs, there is a need for better estimates of both the occurrence and frequency of SVs, preferably from large, ethnically diverse cohorts. Thus, the current standard approach requires the use of short paired-end reads, which remain challenging to detect, especially at the scale of hundreds to thousands of samples. FINDINGS: We present Parliament2, a consensus SV framework that leverages multiple best-in-class methods to identify high-quality SVs from short-read DNA sequence data at scale. Parliament2 incorporates pre-installed SV callers that are optimized for efficient execution in parallel to reduce the overall runtime and costs. We demonstrate the accuracy of Parliament2 when applied to data from NovaSeq and HiSeq X platforms with the Genome in a Bottle (GIAB) SV call set across all size classes. The reported quality score per SV is calibrated across different SV types and size classes. Parliament2 has the highest F1 score (74.27%) measured across the independent gold standard from GIAB. We illustrate the compute performance by processing all 1000 Genomes samples (2,691 samples) in <1 day on GRCH38. Parliament2 improves the runtime performance of individual methods and is open source (https://github.com/slzarate/parliament2), and a Docker image, as well as a WDL implementation, is available. CONCLUSION: Parliament2 provides both a highly accurate single-sample SV call set from short-read DNA sequence data and enables cost-efficient application over cloud or cluster environments, processing thousands of samples.

Paternal mosaicism for a novel PBX1 mutation associated with recurrent perinatal death: Phenotypic expansion of the PBX1-related syndrome. - Arts, Peer; Garland, Jessica; Byrne, Alicia B; Hardy, Tristan S E; Babic, Milena; Feng, Jinghua; Wang, Paul; Ha, Thuong; King-Smith, Sarah L; Schreiber, Andreas W; Crawford, April; Manton, Nick; et al. (Am J Med Genet A, 2020)
Autosomal dominant (de novo) mutations in PBX1 are known to cause congenital abnormalities of the kidney and urinary tract (CAKUT), with or without extra-renal abnormalities. Using trio exome sequencing, we identified a PBX1 p.(Arg107Trp) mutation in a deceased one-day-old neonate presenting with CAKUT, asplenia, and severe bilateral diaphragmatic thinning and eventration. Further investigation by droplet digital PCR revealed that the mutation had occurred post-zygotically in the father, with different variant allele frequencies of the mosaic PBX1 mutation in blood (10%) and sperm (20%). Interestingly, the father had subclinical hydronephrosis in childhood. With an expected recurrence risk of one in five, chorionic villus sampling and prenatal diagnosis for the PBX1 mutation identified recurrence in a subsequent pregnancy. The family opted to continue the pregnancy and the second affected sibling was stillborn at 35 weeks, presenting with similar severe bilateral diaphragmatic eventration, microsplenia, and complete sex reversal (46, XY female). This study highlights the importance of follow-up studies for presumed de novo and low-level mosaic variants and broadens the phenotypic spectrum of developmental abnormalities caused by PBX1 mutations.
Keywords: Congenital Abnormalities; Exome; Fathers; Female; Gene Frequency; Humans; Infant, Newborn; Kidney; Male; Mosaicism; Mutation; Perinatal Death; Pre-B-Cell Leukemia Transcription Factor 1; Pregnancy; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing

Pathogenic Variants in CEP85L Cause Sporadic and Familial Posterior Predominant Lissencephaly. - Tsai, Meng-Han; Muir, Alison M; Wang, Won-Jing; Kang, Yi-Ning; Yang, Kun-Chuan; Chao, Nian-Hsin; Wu, Mei-Feng; Chang, Ying-Chao; Porter, Brenda E; Jansen, Laura A; Sebire, Guillaume; Deconinck, Nicolas; et al. (Neuron, 2020)
Lissencephaly (LIS), denoting a "smooth brain," is characterized by the absence of normal cerebral convolutions with abnormalities of cortical thickness. Pathogenic variants in over 20 genes are associated with LIS. The majority of posterior predominant LIS is caused by pathogenic variants in LIS1 (also known as PAFAH1B1), although a significant fraction remains without a known genetic etiology. We now implicate CEP85L as an important cause of posterior predominant LIS, identifying 13 individuals with rare, heterozygous CEP85L variants, including 2 families with autosomal dominant inheritance. We show that CEP85L is a centrosome protein localizing to the pericentriolar material, and knockdown of Cep85l causes a neuronal migration defect in mice. LIS1 also localizes to the centrosome, suggesting that this organelle is key to the mechanism of posterior predominant LIS.
Keywords: Adolescent; Adult; Age of Onset; Animals; Centrosome; Child; Child, Preschool; Chromosome Aberrations; Classical Lissencephalies and Subcortical Band Heterotopias; Cytoskeletal Proteins; Female; Gene Knockdown Techniques; Genetic Variation; Heterozygote; Humans; Infant; Magnetic Resonance Imaging; Male; Mice; Mutation; Oncogene Proteins, Fusion; Pedigree; Seizures; Young Adult

PEHO syndrome caused by compound heterozygote variants in ZNHIT3 gene. - Õunap, Katrin; Muru, Kai; Õiglane-Shlik, Eve; Ilves, Pilvi; Pajusalu, Sander; Kuus, Imbi; Wojcik, Monica H; Reimand, Tiia (Eur J Med Genet, 2020)
PEHO syndrome is characterized by Progressive Encephalopathy with Edema, Hypsarrhythmia, and Optic atrophy, which was first described in Finnish patients. A homozygous missense substitution p.Ser31Leu in ZNHIT3 was recently identified as the primary cause of PEHO syndrome in Finland. Variants in ZNHIT3 have not been identified in patients with PEHO or PEHO-like syndrome in other populations. It has therefore been suggested that PEHO syndrome caused by ZNHIT3 variants does not occur outside of the Finnish population. We describe the first patient outside Finland who carries compound heterozygous variants in ZNHIT3 gene causing PEHO syndrome. Trio genome sequencing was carried out and the identified variants were confirmed by Sanger sequencing. The patient filled all diagnostic clinical criteria of PEHO syndrome. We identified biallelic missense variants in ZNHIT3 gene: the c.92C > T p.(Ser31Leu) variant (NM_004773.3), which is described previously as causing PEHO syndrome and the second novel variant c.41G > T p.(Cys14Phe). There are only eight heterozygous carriers of c.41G > T variant in the gnomAD database and it is predicted damaging by multiple in silico algorithms. The ZNHIT3-associated PEHO syndrome exists outside of the Finnish population.
Keywords: Brain Edema; Databases, Genetic; Edema; Epileptic Syndromes; Female; Finland; Heterozygote; Humans; Infant, Newborn; Mutation, Missense; Neurodegenerative Diseases; Nuclear Proteins; Optic Atrophy; Phenotype; Spasms, Infantile; Transcription Factors; Whole Exome Sequencing; Whole Genome Sequencing

PhaseME: Automatic rapid assessment of phasing quality and phasing improvement. - Majidian, Sina; Sedlazeck, Fritz J (Gigascience, 2020)
BACKGROUND: The detection of which mutations are occurring on the same DNA molecule is essential to predict their consequences. This can be achieved by phasing the genomic variations. Nevertheless, state-of-the-art haplotype phasing is currently a black box in which the accuracy and quality of the reconstructed haplotypes are hard to assess. FINDINGS: Here we present PhaseME, a versatile method to provide insights into and improvement of sample phasing results based on linkage data. We showcase the performance and the importance of PhaseME by comparing phasing information obtained from Pacific Biosciences including both continuous long reads and high-quality consensus reads, Oxford Nanopore Technologies, 10x Genomics, and Illumina sequencing technologies. We found that 10x Genomics and Oxford Nanopore phasing can be significantly improved while retaining a high N50 and completeness of phase blocks. PhaseME generates reports and summary plots to provide insights into phasing performance and correctness. We observed unique phasing issues for each of the sequencing technologies, highlighting the necessity of quality assessments. PhaseME is able to decrease the Hamming error rate significantly by 22.4% on average across all 5 technologies. Additionally, a significant improvement is obtained in the reduction of long switch errors. Especially for high-quality consensus reads, the improvement is 54.6% in return for only a 5% decrease in phase block N50 length. CONCLUSIONS: PhaseME is a universal method to assess the phasing quality and accuracy and improves the quality of phasing using linkage information. The package is freely available at https://github.com/smajidian/phaseme.

Phenotype expansion of heterozygous FOXC1 pathogenic variants toward involvement of congenital anomalies of the kidneys and urinary tract (CAKUT). - Wu, Chen-Han Wilfred; Mann, Nina; Nakayama, Makiko; Connaughton, Dervla M; Dai, Rufeng; Kolvenbach, Caroline M; Kause, Franziska; Ottlewski, Isabel; Wang, Chunyan; Klämbt, Verena; Seltzsam, Steve; Lai, Ethan W; et al. (Genet Med, 2020)
PURPOSE: Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of chronic kidney disease in childhood and adolescence. We aim to identify novel monogenic causes of CAKUT. METHODS: Exome sequencing was performed in 550 CAKUT-affected families. RESULTS: We discovered seven FOXC1 heterozygous likely pathogenic variants within eight CAKUT families. These variants are either never reported, or present in <5 alleles in the gnomAD database with ~141,456 controls. FOXC1 is a causal gene for Axenfeld-Rieger syndrome type 3 and anterior segment dysgenesis 3. Pathogenic variants in FOXC1 have not been detected in patients with CAKUT yet. Interestingly, mouse models for Foxc1 show severe CAKUT phenotypes with incomplete penetrance and variable expressivity. The FOXC1 variants are enriched in the CAKUT cohort compared with the control. Genotype-phenotype correlations showed that Axenfeld-Rieger syndrome or anterior segment dysgenesis can be caused by both truncating and missense pathogenic variants, and the missense variants are located at the forkhead domain. In contrast, for CAKUT, there is no truncating pathogenic variant, and all variants except one are located outside the forkhead domain. CONCLUSION: We thereby expanded the phenotype of FOXC1 pathogenic variants toward involvement of CAKUT, which can potentially be explained by allelism.
Keywords: Child; Eye Abnormalities; Forkhead Transcription Factors; Heterozygote; Humans; Kidney; Phenotype; Urinary Tract

Phenotypic expansion in KIF1A-related dominant disorders: A description of novel variants and review of published cases. - Montenegro-Garreaud, Ximena; Hansen, Adam W; Khayat, Michael M; Chander, Varuna; Grochowski, Christopher M; Jiang, Yunyun; Li, He; Mitani, Tadahiro; Kessler, Elena; Jayaseelan, Joy; Shen, Hua; Gezdirici, Alper; et al. (Hum Mutat, 2020)
KIF1A is a molecular motor for membrane-bound cargo important to the development and survival of sensory neurons. KIF1A dysfunction has been associated with several Mendelian disorders with a spectrum of overlapping phenotypes, ranging from spastic paraplegia to intellectual disability. We present a novel pathogenic in-frame deletion in the KIF1A molecular motor domain inherited by two affected siblings from an unaffected mother with apparent germline mosaicism. We identified eight additional cases with heterozygous, pathogenic KIF1A variants ascertained from a local data lake. Our data provide evidence for the expansion of KIF1A-associated phenotypes to include hip subluxation and dystonia as well as phenotypes observed in only a single case: gelastic cataplexy, coxa valga, and double collecting system. We review the literature and suggest that KIF1A dysfunction is better understood as a single neuromuscular disorder with variable involvement of other organ systems than a set of discrete disorders converging at a single locus.

Phenotypic expansion of POGZ-related intellectual disability syndrome (White-Sutton syndrome). - Assia Batzir, Nurit; Posey, Jennifer E; Song, Xiaofei; Akdemir, Zeynep Coban; Rosenfeld, Jill A; Brown, Chester W; Chen, Emily; Holtrop, Shannon G; Mizerik, Elizabeth; Nieto Moreno, Margarita; Payne, Katelyn; Raas-Rothschild, Annick; et al. (Am J Med Genet A, 2020)
White-Sutton syndrome (WHSUS) is a recently-identified genetic disorder resulting from de novo heterozygous pathogenic variants in POGZ. Thus far, over 50 individuals have been reported worldwide, however phenotypic characterization and data regarding the natural history are still incomplete. Here we report the clinical features of 22 individuals with 21 unique loss of function POGZ variants. We observed a broad spectrum of intellectual disability and/or developmental delay with or without autism, and speech delay in all individuals. Other common problems included ocular abnormalities, hearing loss and gait abnormalities. A validated sleep disordered breathing questionnaire identified symptoms of obstructive sleep apnea in 4/12 (33%) individuals. A higher-than-expected proportion of cases also had gastrointestinal phenotypes, both functional and anatomical, as well as genitourinary anomalies. In line with previous publications, we observed an increased body mass index (BMI) z-score compared to the general population (mean 0.59, median 0.9; p 0.0253). Common facial features included microcephaly, broad forehead, midface hypoplasia, triangular mouth, broad nasal root and flat nasal bridge. Analysis of the Baylor Genetics clinical laboratory database revealed that POGZ variants were implicated in approximately 0.14% of cases who underwent clinical exome sequencing for neurological indications with or without involvement of other body systems. This study describes a greater allelic series and expands the phenotypic spectrum of this new syndromic form of intellectual disability and autism.
Keywords: Adolescent; Adult; Autistic Disorder; Child; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Microcephaly; Middle Aged; Mutation; Phenotype; Transposases; Whole Exome Sequencing; Young Adult

Phenotypic spectrum and transcriptomic profile associated with germline variants in TRAF7. - Castilla-Vallmanya, Laura; Selmer, Kaja K; Dimartino, Clémantine; Rabionet, Raquel; Blanco-Sánchez, Bernardo; Yang, Sandra; Reijnders, Margot R F; van Essen, Antonie J; Oufadem, Myriam; Vigeland, Magnus D; Stadheim, Barbro; Houge, Gunnar; et al. (Genet Med, 2020)
PURPOSE: Somatic variants in tumor necrosis factor receptor-associated factor 7 (TRAF7) cause meningioma, while germline variants have recently been identified in seven patients with developmental delay and cardiac, facial, and digital anomalies. We aimed to define the clinical and mutational spectrum associated with TRAF7 germline variants in a large series of patients, and to determine the molecular effects of the variants through transcriptomic analysis of patient fibroblasts. METHODS: We performed exome, targeted capture, and Sanger sequencing of patients with undiagnosed developmental disorders, in multiple independent diagnostic or research centers. Phenotypic and mutational comparisons were facilitated through data exchange platforms. Whole-transcriptome sequencing was performed on RNA from patient- and control-derived fibroblasts. RESULTS: We identified heterozygous missense variants in TRAF7 as the cause of a developmental delay-malformation syndrome in 45 patients. Major features include a recognizable facial gestalt (characterized in particular by blepharophimosis), short neck, pectus carinatum, digital deviations, and patent ductus arteriosus. Almost all variants occur in the WD40 repeats and most are recurrent. Several differentially expressed genes were identified in patient fibroblasts. CONCLUSION: We provide the first large-scale analysis of the clinical and mutational spectrum associated with the TRAF7 developmental syndrome, and we shed light on its molecular etiology through transcriptome studies.
Keywords: Exome; Germ Cells; Humans; Intellectual Disability; Mutation, Missense; Phenotype; Transcriptome; Tumor Necrosis Factor Receptor-Associated Peptides and Proteins

The pleiotropy associated with de novo variants in CHD4, CNOT3, and SETD5 extends to moyamoya angiopathy. - Pinard, Amelie; Guey, Stéphanie; Guo, Dongchuan; Cecchi, Alana C; Kharas, Natasha; Wallace, Stephanie; Regalado, Ellen S; Hostetler, Ellen M; Sharrief, Anjail Z; Bergametti, Françoise; Kossorotoff, Manoelle; Hervé, Dominique; et al. (Genet Med, 2020)
PURPOSE: Moyamoya angiopathy (MMA) is a cerebrovascular disease characterized by occlusion of large arteries, which leads to strokes starting in childhood. Twelve altered genes predispose to MMA but the majority of cases of European descent do not have an identified genetic trigger. METHODS: Exome sequencing from 39 trios were analyzed. RESULTS: We identified four de novo variants in three genes not previously associated with MMA: CHD4, CNOT3, and SETD5. Identification of additional rare variants in these genes in 158 unrelated MMA probands provided further support that rare pathogenic variants in CHD4 and CNOT3 predispose to MMA. Previous studies identified de novo variants in these genes in children with developmental disorders (DD), intellectual disability, and congenital heart disease. CONCLUSION: These genes encode proteins involved in chromatin remodeling, and taken together with previously reported genes leading to MMA-like cerebrovascular occlusive disease (YY1AP1, SMARCAL1), implicate disrupted chromatin remodeling as a molecular pathway predisposing to early onset, large artery occlusive cerebrovascular disease. Furthermore, these data expand the spectrum of phenotypic pleiotropy due to alterations of CHD4, CNOT3, and SETD5 beyond DD to later onset disease in the cerebrovascular arteries and emphasize the need to assess clinical complications into adulthood for genes associated with DD.
Keywords: Adult; Cell Cycle Proteins; Cerebrovascular Disorders; Child; Child, Preschool; Developmental Disabilities; DNA Helicases; Exome; Female; Genetic Predisposition to Disease; Humans; Intellectual Disability; Male; Methyltransferases; Mi-2 Nucleosome Remodeling and Deacetylase Complex; Middle Aged; Moyamoya Disease; Mutation; Nuclear Proteins; Transcription Factors; Whole Exome Sequencing

POGLUT1 biallelic mutations cause myopathy with reduced satellite cells, α-dystroglycan hypoglycosylation and a distinctive radiological pattern. - Servián-Morilla, E; Cabrera-Serrano, M; Johnson, K; Pandey, A; Ito, A; Rivas, E; Chamova, T; Muelas, N; Mongini, T; Nafissi, S; Claeys, K G; Grewal, R P; et al. (Acta Neuropathol, 2020)
Protein O-glucosyltransferase 1 (POGLUT1) activity is critical for the Notch signaling pathway, being one of the main enzymes responsible for the glycosylation of the extracellular domain of Notch receptors. A biallelic mutation in the POGLUT1 gene has been reported in one family as the cause of an adult-onset limb-girdle muscular dystrophy (LGMD R21; OMIM# 617232). As the result of a collaborative international effort, we have identified the first cohort of 15 patients with LGMD R21, from nine unrelated families coming from different countries, providing a reliable phenotype-genotype and mechanistic insight. Patients carrying novel mutations in POGLUT1 all displayed a clinical picture of limb-girdle muscle weakness. However, the age at onset was broadened from adult to congenital and infantile onset. Moreover, we now report that the unique muscle imaging pattern of "inside-to-outside" fatty degeneration observed in the original cases is indeed a defining feature of POGLUT1 muscular dystrophy. Experiments on muscle biopsies from patients revealed a remarkable and consistent decrease in the level of the NOTCH1 intracellular domain, reduction of the pool of satellite cells (SC), and evidence of α-dystroglycan hypoglycosylation. In vitro biochemical and cell-based assays suggested a pathogenic role of the novel POGLUT1 mutations, leading to reduced enzymatic activity and/or protein stability. The association between the POGLUT1 variants and the muscular phenotype was established by in vivo experiments analyzing the indirect flight muscle development in transgenic Drosophila, showing that the human POGLUT1 mutations reduced its myogenic activity. In line with the well-known role of the Notch pathway in the homeostasis of SC and muscle regeneration, SC-derived myoblasts from patients' muscle samples showed decreased proliferation and facilitated differentiation. Together, these observations suggest that alterations in SC biology caused by reduced Notch1 signaling result in muscular dystrophy in LGMD R21 patients, likely with additional contribution from α-dystroglycan hypoglycosylation. This study settles the muscular clinical phenotype linked to POGLUT1 mutations and establishes the pathogenic mechanism underlying this muscle disorder. The description of a specific imaging pattern of fatty degeneration and muscle pathology with a decrease of α-dystroglycan glycosylation provides excellent tools which will help diagnose and follow up LGMD R21 patients.
Keywords: Animals; Animals, Genetically Modified; Drosophila melanogaster; Dystroglycans; Female; Genetic Association Studies; Glucosyltransferases; Glycosylation; Humans; Male; Muscle, Skeletal; Muscular Dystrophies, Limb-Girdle; Mutation; Pedigree; Satellite Cells, Skeletal Muscle

Polygenic background modifies penetrance of monogenic variants for tier 1 genomic conditions. - Fahed, Akl C; Wang, Minxian; Homburger, Julian R; Patel, Aniruddh P; Bick, Alexander G; Neben, Cynthia L; Lai, Carmen; Brockman, Deanna; Philippakis, Anthony; Ellinor, Patrick T; Cassa, Christopher A; Lebo, Matthew; et al. (Nat Commun, 2020)
Genetic variation can predispose to disease both through (i) monogenic risk variants that disrupt a physiologic pathway with large effect on disease and (ii) polygenic risk that involves many variants of small effect in different pathways. Few studies have explored the interplay between monogenic and polygenic risk. Here, we study 80,928 individuals to examine whether polygenic background can modify penetrance of disease in tier 1 genomic conditions - familial hypercholesterolemia, hereditary breast and ovarian cancer, and Lynch syndrome. Among carriers of a monogenic risk variant, we estimate substantial gradients in disease risk based on polygenic background - the probability of disease by age 75 years ranged from 17% to 78% for coronary artery disease, 13% to 76% for breast cancer, and 11% to 80% for colon cancer. We propose that accounting for polygenic background is likely to increase accuracy of risk estimation for individuals who inherit a monogenic risk variant.
Keywords: Aged; Breast Neoplasms; Case-Control Studies; Colorectal Neoplasms; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome, Human; Humans; Male; Middle Aged; Multifactorial Inheritance; Odds Ratio; Penetrance; Risk Factors

Polymicrogyria is Associated With Pathogenic Variants in PTEN. - Shao, Diane D; Achkar, Christelle M; Lai, Abbe; Srivastava, Siddharth; Doan, Ryan N; Rodan, Lance H; Chen, Allen Y; Poduri, Annapurna; Yang, Edward; Walsh, Christopher A (Ann Neurol, 2020)
OBJECTIVE: Congenital structural brain malformations have been described in patients with pathogenic phosphatase and tensin homologue (PTEN) variants, but the frequency of cortical malformations in patients with PTEN variants and their impact on clinical phenotype are not well understood. Our goal was to systematically characterize brain malformations in patients with PTEN variants and assess the relevance of their brain malformations to clinical presentation. METHODS: We systematically searched a local radiology database for patients with PTEN variants who had available brain magnetic resonance imaging (MRI). The MRI scans were reviewed systematically for cortical abnormalities. We reviewed electroencephalogram (EEG) data and evaluated the electronic medical record for evidence of epilepsy and developmental delay. RESULTS: In total, we identified 22 patients with PTEN pathogenic variants for which brain MRIs were available (age range 0.4-17 years). Twelve among these 22 patients (54%) had polymicrogyria (PMG). Variants associated with PMG or atypical gyration encoded regions of the phosphatase or C2 domains of PTEN. Interestingly, epilepsy was present in only 2 of the 12 patients with PMG. We found a trend toward higher rates of global developmental delay (GDD), intellectual disability (ID), and motor delay in individuals with cortical abnormalities, although cohort size limited statistical significance. INTERPRETATION: Malformations of cortical development, PMG in particular, represent an under-recognized phenotype associated with PTEN pathogenic variants and may have an association with cognitive and motor delays. Epilepsy was infrequent compared to the previously reported high risk of epilepsy in patients with PMG. ANN NEUROL 2020;88:1153-1164.
Keywords: Adolescent; Brain; Child; Child, Preschool; Comorbidity; Databases, Genetic; Developmental Disabilities; Electroencephalography; Female; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Massachusetts; Neuroimaging; Polymicrogyria; PTEN Phosphohydrolase

Posterior Neocortex-Specific Regulation of Neuronal Migration by CEP85L Identifies Maternal Centriole-Dependent Activation of CDK5. - Kodani, Andrew; Kenny, Connor; Lai, Abbe; Gonzalez, Dilenny M; Stronge, Edward; Sejourne, Gabrielle M; Isacco, Laura; Partlow, Jennifer N; O'Donnell, Anne; McWalter, Kirsty; Byrne, Alicia B; Barkovich, A James; et al. (Neuron, 2020)
Genes mutated in human neuronal migration disorders encode tubulin proteins and a variety of tubulin-binding and -regulating proteins, but it is very poorly understood how these proteins function together to coordinate migration. Additionally, the way in which regional differences in neocortical migration are controlled is completely unknown. Here we describe a new syndrome with remarkably region-specific effects on neuronal migration in the posterior cortex, reflecting de novo variants in CEP85L. We show that CEP85L is required cell autonomously in vivo and in vitro for migration, that it localizes to the maternal centriole, and that it forms a complex with many other proteins required for migration, including CDK5, LIS1, NDE1, KIF2A, and DYNC1H1. Loss of CEP85L disrupts CDK5 localization and activation, leading to centrosome disorganization and disrupted microtubule cytoskeleton organization. Together, our findings suggest that CEP85L highlights a complex that controls CDK5 activity to promote neuronal migration.
Keywords: Cell Movement; Centrioles; Child; Child, Preschool; Cyclin-Dependent Kinase 5; Cytoskeletal Proteins; Female; Humans; Lissencephaly; Male; Microtubules; Neocortex; Nerve Tissue Proteins; Neurons; Oncogene Proteins, Fusion; Young Adult

Post-zygotic ACTB mutations underlie congenital smooth muscle hamartomas. - Atzmony, Lihi; Ugwu, Nelson; Zaki, Theodore D; Antaya, Richard J; Choate, Keith A (J Cutan Pathol, 2020)
BACKGROUND: Congenital smooth muscle hamartomas (CSMHs) are benign lesions that share clinical and histopathological features with Becker nevus, a mosaic disorder associated with post-zygotic ACTB mutations. Given the clinical and histopathological overlap between CSMH and Becker nevus, we hypothesized that post-zygotic mutations in ACTB may underlie CSMH. METHODS: Direct sequencing of ACTB gene in affected and unaffected tissue isolated from one case of hemihypertrichosis and hemihypertrophy corresponding to giant segmental CSMH and hemihypertrophy. This was followed by direct sequencing with and without enrichment assay for hotspot ACTB mutations in affected tissue from 12 samples of isolated CSMH from unrelated individuals. RESULTS: In total we identified somatic missense ACTB mutations in 9 out of 13 CSMHs (69%). Mutations were either novel or previously reported in Becker nevi and Becker nevus syndrome. CONCLUSIONS: CSMHs result from post-zygotic ACTB mutations. This study proves that CSMHs and Becker nevi are nosologically related, and expand the phenotypic spectrum of ACTB mutations.

Predominant and novel de novo variants in 29 individuals with ALG13 deficiency: Clinical description, biomarker status, biochemical analysis, and treatment suggestions. - Ng, Bobby G; Eklund, Erik A; Shiryaev, Sergey A; Dong, Yin Y; Abbott, Mary-Alice; Asteggiano, Carla; Bamshad, Michael J; Barr, Eileen; Bernstein, Jonathan A; Chelakkadan, Shabeed; Christodoulou, John; Chung, Wendy K; et al. (J Inherit Metab Dis, 2020)
Asparagine-linked glycosylation 13 homolog (ALG13) encodes a nonredundant, highly conserved, X-linked uridine diphosphate (UDP)-N-acetylglucosaminyltransferase required for the synthesis of lipid linked oligosaccharide precursor and proper N-linked glycosylation. De novo variants in ALG13 underlie a form of early infantile epileptic encephalopathy known as EIEE36, but given its essential role in glycosylation, it is also considered a congenital disorder of glycosylation (CDG), ALG13-CDG. Twenty-four previously reported ALG13-CDG cases had de novo variants, but surprisingly, unlike most forms of CDG, ALG13-CDG did not show the anticipated glycosylation defects, typically detected by altered transferrin glycosylation. Structural homology modeling of two recurrent de novo variants, p.A81T and p.N107S, suggests both are likely to impact the function of ALG13. Using a corresponding ALG13-deficient yeast strain, we show that expressing yeast ALG13 with either of the highly conserved hotspot variants rescues the observed growth defect, but not its glycosylation abnormality. We present molecular and clinical data on 29 previously unreported individuals with de novo variants in ALG13. This more than doubles the number of known cases. A key finding is that a vast majority of the individuals presents with West syndrome, a feature shared with other CDG types. Among these, the initial epileptic spasms best responded to adrenocorticotropic hormone or prednisolone, while clobazam and felbamate showed promise for continued epilepsy treatment. A ketogenic diet seems to play an important role in the treatment of these individuals.

Prenatal Diagnosis of a Ventral Abdominal Wall Defect. - Beam, Kristyn; Wojcik, Monica H; Agrawal, Pankaj B; Smithers, Charles; Estroff, Judy (Neoreviews, 2020)
Keywords: Abnormalities, Multiple; Echocardiography; Fatal Outcome; Female; Hernia, Abdominal; Hernia, Diaphragmatic; Hernia, Ventral; Humans; Infant, Newborn; Magnetic Resonance Imaging; Pregnancy; Prenatal Diagnosis; Ultrasonography, Prenatal

Quantitative Assessment of Parental Somatic Mosaicism for Copy-Number Variant (CNV) Deletions. - Liu, Qian; Grochowski, Christopher M; Bi, Weimin; Lupski, James R; Stankiewicz, Paweł (Curr Protoc Hum Genet, 2020)
As genome sequencing methodologies have become more sensitive in detecting low-frequency rare-variant events, the link between post-zygotic mutagenesis and somatic mosaicism in the etiology of several human genetic conditions other than cancers has become more clear. Given that current clinical-genomics diagnostic methods have limited detection sensitivity for mosaic events, a copy-number variant (CNV) deletion inherited from a parent with low-level (<10%) mosaicism can be erroneously interpreted in the proband to represent a de novo germline event. Here, we describe three sensitive, precise, and cost-efficient methods that can quantitatively assess the potential degree of parental somatic mosaicism levels for CNV deletions: droplet digital PCR (ddPCR), PCR amplicon-based next-generation sequencing (NGS), and quantitative PCR. ddPCR using the EvaGreen fluorescent dye protocol can specifically quantify the deleted or non-deleted alleles by analyzing the number of droplets positive for a fluorescent signal for each event. PCR amplicon-based NGS assesses the allele frequencies of a heterozygous single-nucleotide polymorphism within a deletion region. The difference in number of reads between the two genotypes indicates the level of somatic mosaicism for the CNV deletion. Quantitative PCR can be applied where the relative quantity of the deletion junction-specific product represents the level of mosaicism. Clinical implementation of these quantitative variant-detection methods enables potentially more accurate assessment of disease recurrence risk in family-based genetic counseling, allowing couples to engage in more informed family planning. © 2020 by John Wiley & Sons, Inc. Basic Protocol: Droplet digital PCR (ddPCR) Alternate Protocol 1: PCR amplicon-based next-generation sequencing Alternate Protocol 2: Quantitative real-time PCR (qPCR).
Keywords: DNA Copy Number Variations; Genetic Diseases, Inborn; High-Throughput Nucleotide Sequencing; Humans; Mosaicism; Parents; Polymorphism, Single Nucleotide; Real-Time Polymerase Chain Reaction

Rapid, Paralog-Sensitive CNV Analysis of 2457 Human Genomes Using QuicK-mer2. - Shen, Feichen; Kidd, Jeffrey M (Genes (Basel), 2020)
Gene duplication is a major mechanism for the evolution of gene novelty, and copy-number variation makes a major contribution to inter-individual genetic diversity. However, most approaches for studying copy-number variation rely upon uniquely mapping reads to a genome reference and are unable to distinguish among duplicated sequences. Specialized approaches to interrogate specific paralogs are comparatively slow and have a high degree of computational complexity, limiting their effective application to emerging population-scale data sets. We present QuicK-mer2, a self-contained, mapping-free approach that enables the rapid construction of paralog-specific copy-number maps from short-read sequence data. This approach is based on the tabulation of unique k-mer sequences from short-read data sets, and is able to analyze a 20X coverage human genome in approximately 20 min. We applied our approach to newly released sequence data from the 1000 Genomes Project, constructed paralog-specific copy-number maps from 2457 unrelated individuals, and uncovered copy-number variation of paralogous genes. We identify nine genes where none of the analyzed samples have a copy number of two, 92 genes where the majority of samples have a copy number other than two, and describe rare copy number variation effecting multiple genes at the APOBEC3 locus.
Keywords: Algorithms; Computational Biology; DNA Copy Number Variations; Evolution, Molecular; Gene Duplication; Genome, Human; Humans; Sequence Analysis, DNA

Rare deleterious variants of NOTCH1, GATA4, SMAD6, and ROBO4 are enriched in BAV with early onset complications but not in BAV with heritable thoracic aortic disease. - Musfee, Fadi I; Guo, Dongchuan; Pinard, Amélie C; Hostetler, Ellen M; Blue, Elizabeth E; Nickerson, Deborah A; Bamshad, Michael J; Milewicz, Dianna M; Prakash, Siddharth K (Mol Genet Genomic Med, 2020)
BACKGROUND: Bicuspid aortic valve (BAV) is the most common cardiovascular malformation in adults, with a prevalence of 0.5%-2%. The prevalence of BAV in cohorts who were ascertained due to thoracic aortic aneurysms or acute aortic dissections (TAD) is as high as 20%. However, the contribution of causal BAV genes to TAD is not known. Therefore, we evaluated rare deleterious variants of GATA4, NOTCH1, SMAD6, or ROBO4 in patients with BAV who presented with TAD. METHODS: Our cohort consisted of 487 probands with Heritable Thoracic Aortic Aneurysms or Dissections (HTAD, 12% BAV, 29% female) and 63 probands with Early onset complications of Bicuspid Aortic Valve disease (EBAV, 63% TAD, 34% female). After whole exome sequencing, we functionally annotated GATA4, NOTCH1, SMAD6, and ROBO4 variants and compared the prevalence of rare variants in these genes to controls without HTAD. RESULTS: We identified 11 rare deleterious variants of GATA4, SMAD6, or ROBO4 in 12 (18%) EBAV cases. The burden of rare SMAD6 and GATA4 variants was significantly enriched in EBAV but not in HTAD cases, even among HTAD cases with BAV (p < .003). CONCLUSION: Rare variants of NOTCH1, ROBO4, SMAD6, or GATA4 do not significantly contribute to BAV in cohorts with HTAD. We conclude that BAV patients who present with HTAD are a genetically distinct subgroup with implications for genetic testing and prognosis.
Keywords: Adult; Aortic Aneurysm, Thoracic; Bicuspid Aortic Valve Disease; Female; GATA4 Transcription Factor; Gene Frequency; Humans; Male; Middle Aged; Mutation; Receptor, Notch1; Receptors, Cell Surface; Smad6 Protein

Recurrent arginine substitutions in the ACTG2 gene are the primary driver of disease burden and severity in visceral myopathy. - Assia Batzir, Nurit; Kishor Bhagwat, Pranjali; Larson, Austin; Coban Akdemir, Zeynep; Bagłaj, Maciej; Bofferding, Leon; Bosanko, Katherine B; Bouassida, Skander; Callewaert, Bert; Cannon, Ashley; Enchautegui Colon, Yazmin; Garnica, Adolfo D; et al. (Hum Mutat, 2020)
Visceral myopathy with abnormal intestinal and bladder peristalsis includes a clinical spectrum with megacystis-microcolon intestinal hypoperistalsis syndrome and chronic intestinal pseudo-obstruction. The vast majority of cases are caused by dominant variants in ACTG2; however, the overall genetic architecture of visceral myopathy has not been well-characterized. We ascertained 53 families, with visceral myopathy based on megacystis, functional bladder/gastrointestinal obstruction, or microcolon. A combination of targeted ACTG2 sequencing and exome sequencing was used. We report a molecular diagnostic rate of 64% (34/53), of which 97% (33/34) is attributed to ACTG2. Strikingly, missense mutations in five conserved arginine residues involving CpG dinucleotides accounted for 49% (26/53) of disease in the cohort. As a group, the ACTG2-negative cases had a more favorable clinical outcome and more restricted disease. Within the ACTG2-positive group, poor outcomes (characterized by total parenteral nutrition dependence, death, or transplantation) were invariably due to one of the arginine missense alleles. Analysis of specific residues suggests a severity spectrum of p.Arg178>p.Arg257>p.Arg40 along with other less-frequently reported sites p.Arg63 and p.Arg211. These results provide genotype-phenotype correlation for ACTG2-related disease and demonstrate the importance of arginine missense changes in visceral myopathy.

Recurrent De Novo NAHR Reciprocal Duplications in the ATAD3 Gene Cluster Cause a Neurogenetic Trait with Perturbed Cholesterol and Mitochondrial Metabolism. - Gunning, Adam C; Strucinska, Klaudia; Muñoz Oreja, Mikel; Parrish, Andrew; Caswell, Richard; Stals, Karen L; Durigon, Romina; Durlacher-Betzer, Karina; Cunningham, Mitchell H; Grochowski, Christopher M; Baptista, Julia; Tysoe, Carolyn; et al. (Am J Hum Genet, 2020)
Recent studies have identified both recessive and dominant forms of mitochondrial disease that result from ATAD3A variants. The recessive form includes subjects with biallelic deletions mediated by non-allelic homologous recombination. We report five unrelated neonates with a lethal metabolic disorder characterized by cardiomyopathy, corneal opacities, encephalopathy, hypotonia, and seizures in whom a monoallelic reciprocal duplication at the ATAD3 locus was identified. Analysis of the breakpoint junction fragment indicated that these 67 kb heterozygous duplications were likely mediated by non-allelic homologous recombination at regions of high sequence identity in ATAD3A exon 11 and ATAD3C exon 7. At the recombinant junction, the duplication allele produces a fusion gene derived from ATAD3A and ATAD3C, the protein product of which lacks key functional residues. Analysis of fibroblasts derived from two affected individuals shows that the fusion gene product is expressed and stable. These cells display perturbed cholesterol and mitochondrial DNA organization similar to that observed for individuals with severe ATAD3A deficiency. We hypothesize that the fusion protein acts through a dominant-negative mechanism to cause this fatal mitochondrial disorder. Our data delineate a molecular diagnosis for this disorder, extend the clinical spectrum associated with structural variation at the ATAD3 locus, and identify a third mutational mechanism for ATAD3 gene cluster variants. These results further affirm structural variant mutagenesis mechanisms in sporadic disease traits, emphasize the importance of copy number analysis in molecular genomic diagnosis, and highlight some of the challenges of detecting and interpreting clinically relevant rare gene rearrangements from next-generation sequencing data.
Keywords: Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Brain Diseases; Cardiomyopathies; Cholesterol; Corneal Opacity; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Homologous Recombination; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Diseases; Mitochondrial Proteins; Muscle Hypotonia; Mutation; Protein Conformation; Seizures; Sequence Homology

Recurrent homozygous damaging mutation in , encoding a protein disulfide isomerase, in four families with microlissencephaly. - Ghosh, Shereen Georges; Wang, Lu; Breuss, Martin W; Green, Joshua D; Stanley, Valentina; Yang, Xiaoxu; Ross, Danica; Traynor, Bryan J; Alhashem, Amal M; Azam, Matloob; Selim, Laila; Bastaki, Laila; et al. (J Med Genet, 2020)
BACKGROUND: Protein disulfide isomerase (PDI) proteins are part of the thioredoxin protein superfamily. PDIs are involved in the formation and rearrangement of disulfide bonds between cysteine residues during protein folding in the endoplasmic reticulum and are implicated in stress response pathways. METHODS: Eight children from four consanguineous families residing in distinct geographies within the Middle East and Central Asia were recruited for study. All probands showed structurally similar microcephaly with lissencephaly (microlissencephaly) brain malformations. DNA samples from each family underwent whole exome sequencing, assessment for repeat expansions and confirmatory segregation analysis. RESULTS: An identical homozygous variant in (c.500G>A), encoding thioredoxin-related transmembrane protein 2, segregated with disease in all four families. This variant changed the last coding base of exon 6, and impacted mRNA stability. All patients presented with microlissencephaly, global developmental delay, intellectual disability and epilepsy. While is an activator of cellular repeat expansion toxicity, patients showed no evidence of repeat expansions. CONCLUSION: The c.500G>A allele associates with recessive microlissencephaly, and patients show no evidence of expansions. is the first PDI implicated in a recessive disease, suggesting a protein isomerisation defect in microlissencephaly.
Keywords: Amino Acid Sequence; Child; Child, Preschool; Consanguinity; Endoplasmic Reticulum; Exons; Female; Genetic Predisposition to Disease; Homozygote; Humans; Male; Membrane Proteins; Microcephaly; Mutation; Protein Disulfide-Isomerases; Protein Folding; Thioredoxins; Whole Exome Sequencing

Recurrent Rare Copy Number Variants Increase Risk for Esotropia. - Whitman, Mary C; Di Gioia, Silvio Alessandro; Chan, Wai-Man; Gelber, Alon; Pratt, Brandon M; Bell, Jessica L; Collins, Thomas E; Knowles, James A; Armoskus, Christopher; Pato, Michele; Pato, Carlos; Shaaban, Sherin; et al. (Invest Ophthalmol Vis Sci, 2020)
Purpose: To determine whether rare copy number variants (CNVs) increase risk for comitant esotropia. Methods: CNVs were identified in 1614 Caucasian individuals with comitant esotropia and 3922 Caucasian controls from Illumina SNP genotyping using two Hidden Markov model (HMM) algorithms, PennCNV and QuantiSNP, which call CNVs based on logR ratio and B allele frequency. Deletions and duplications greater than 10 kb were included. Common CNVs were excluded. Association testing was performed with 1 million permutations in PLINK. Significant CNVs were confirmed with digital droplet polymerase chain reaction (ddPCR). Whole genome sequencing was performed to determine insertion location and breakpoints. Results: Esotropia patients have similar rates and proportions of CNVs compared with controls but greater total length and average size of both deletions and duplications. Three recurrent rare duplications significantly (P = 1 × 10-6) increase the risk of esotropia: chromosome 2p11.2 (hg19, 2:87428677-87965359), spanning one long noncoding RNA (lncRNA) and two microRNAs (OR 14.16; 95% confidence interval [CI] 5.4-38.1); chromosome 4p15.2 (hg19, 4:25554332-25577184), spanning one lncRNA (OR 11.1; 95% CI 4.6-25.2); chromosome 10q11.22 (hg19, 10:47049547-47703870) spanning seven protein-coding genes, one lncRNA, and four pseudogenes (OR 8.96; 95% CI 5.4-14.9). Overall, 114 cases (7%) and only 28 controls (0.7%) had one of the three rare duplications. No case nor control had more than one of these three duplications. Conclusions: Rare CNVs are a source of genetic variation that contribute to the genetic risk for comitant esotropia, which is likely polygenic. Future research into the functional consequences of these recurrent duplications may shed light on the pathophysiology of esotropia.
Keywords: Case-Control Studies; DNA Copy Number Variations; Esotropia; Female; Gene Duplication; Gene Frequency; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Infant; Male; Markov Chains; Polymerase Chain Reaction; Risk Factors

Recurrent TTN metatranscript-only c.39974-11T>G splice variant associated with autosomal recessive arthrogryposis multiplex congenita and myopathy. - Bryen, Samantha J; Ewans, Lisa J; Pinner, Jason; MacLennan, Suzanna C; Donkervoort, Sandra; Castro, Diana; Topf, Ana; O'Grady, Gina; Cummings, Beryl; Chao, Katherine R; Weisburd, Ben; Francioli, Laurent; et al. (Hum Mutat, 2020)
We present eight families with arthrogryposis multiplex congenita and myopathy bearing a TTN intron 213 extended splice-site variant (NM_001267550.1:c.39974-11T>G), inherited in trans with a second pathogenic TTN variant. Muscle-derived RNA studies of three individuals confirmed mis-splicing induced by the c.39974-11T>G variant; in-frame exon 214 skipping or use of a cryptic 3' splice-site effecting a frameshift. Confounding interpretation of pathogenicity is the absence of exons 213-217 within the described skeletal muscle TTN N2A isoform. However, RNA-sequencing from 365 adult human gastrocnemius samples revealed that 56% specimens predominantly include exons 213-217 in TTN transcripts (inclusion rate ≥66%). Further, RNA-sequencing of five fetal muscle samples confirmed that 4/5 specimens predominantly include exons 213-217 (fifth sample inclusion rate 57%). Contractures improved significantly with age for four individuals, which may be linked to decreased expression of pathogenic fetal transcripts. Our study extends emerging evidence supporting a vital developmental role for TTN isoforms containing metatranscript-only exons.

Regulation of human cerebral cortical development by EXOC7 and EXOC8, components of the exocyst complex, and roles in neural progenitor cell proliferation and survival. - Coulter, Michael E; Musaev, Damir; DeGennaro, Ellen M; Zhang, Xiaochang; Henke, Katrin; James, Kiely N; Smith, Richard S; Hill, R Sean; Partlow, Jennifer N; Kamumbu, A Stacy; Hatem, Nicole; Barkovich, A James; et al. (Genet Med, 2020)
PURPOSE: The exocyst complex is a conserved protein complex that mediates fusion of intracellular vesicles to the plasma membrane and is implicated in processes including cell polarity, cell migration, ciliogenesis, cytokinesis, autophagy, and fusion of secretory vesicles. The essential role of these genes in human genetic disorders, however, is unknown. METHODS: We performed homozygosity mapping and exome sequencing of consanguineous families with recessively inherited brain development disorders. We modeled an EXOC7 splice variant in vitro and examined EXOC7 messenger RNA (mRNA) expression in developing mouse and human cortex. We modeled exoc7 loss-of-function in a zebrafish knockout. RESULTS: We report variants in exocyst complex members, EXOC7 and EXOC8, in a novel disorder of cerebral cortex development. In EXOC7, we identified four independent partial loss-of-function (LOF) variants in a recessively inherited disorder characterized by brain atrophy, seizures, and developmental delay, and in severe cases, microcephaly and infantile death. In EXOC8, we found a homozygous truncating variant in a family with a similar clinical disorder. We modeled exoc7 deficiency in zebrafish and found the absence of exoc7 causes microcephaly. CONCLUSION: Our results highlight the essential role of the exocyst pathway in normal cortical development and how its perturbation causes complex brain disorders.
Keywords: Animals; Brain Diseases; Cell Proliferation; Homozygote; Humans; Mice; Microcephaly; Zebrafish

-related autosomal recessive encephalopathy in 2 Turkish children. - Yaramis, Ahmet; Lochmüller, Hanns; Topf, Ana; Sonmezler, Ece; Yilmaz, Elmasnur; Hiz, Semra; Yis, Uluc; Güngör, Serdal; Ipek Polat, Ayse; Edem, Pinar; Beltran, Sergi; Laurie, Steven; et al. (Neurol Genet, 2020)
Objective: This study presents the neurologic phenotypes of 2 brothers with a novel homozygous mutation that was identified in a large Turkish consanguineous cohort of neurogenetic diseases. Methods: Whole-exome sequencing and bioinformatic analysis of consanguineous families with children affected by early-onset, neurogenetic disorders was performed using the RD-Connect Genome-Phenome Analysis Platform. We also performed clinical, EEG, and neuroimaging analyses in unaffected siblings and parents. Results: We have identified a homozygous missense mutation in (p.Gly1278Ser, NM_001845.5:c.3832G>T) in 2 siblings affected by small vessel brain disease with periventricular leukoencephalopathy and ocular defects. Presenting symptoms included mild weakness, hemiparetic gait, pyramidal findings, and seizures, whereas their intellectual and behavioral functions were normal. Both parents and 5 of the siblings (3 boys and 2 girls) were heterozygous for the variant. They did not show any clinical or laboratory signs of small vessel disease. Conclusions: has previously been associated with dominant small vessel disease of the brain and other organs, manifesting with high penetrance in heterozygous mutation carriers. Our findings provide evidence that -related encephalopathy can be inherited in an autosomal recessive manner, which is important for counseling, prognosis, and treatment. Genotype-phenotype correlations remain to be established.

RNA Identification of PRIME Cells Predicting Rheumatoid Arthritis Flares. - Orange, Dana E; Yao, Vicky; Sawicka, Kirsty; Fak, John; Frank, Mayu O; Parveen, Salina; Blachere, Nathalie E; Hale, Caryn; Zhang, Fan; Raychaudhuri, Soumya; Troyanskaya, Olga G; Darnell, Robert B (N Engl J Med, 2020)
BACKGROUND: Rheumatoid arthritis, like many inflammatory diseases, is characterized by episodes of quiescence and exacerbation (flares). The molecular events leading to flares are unknown. METHODS: We established a clinical and technical protocol for repeated home collection of blood in patients with rheumatoid arthritis to allow for longitudinal RNA sequencing (RNA-seq). Specimens were obtained from 364 time points during eight flares over a period of 4 years in our index patient, as well as from 235 time points during flares in three additional patients. We identified transcripts that were differentially expressed before flares and compared these with data from synovial single-cell RNA-seq. Flow cytometry and sorted-blood-cell RNA-seq in additional patients were used to validate the findings. RESULTS: Consistent changes were observed in blood transcriptional profiles 1 to 2 weeks before a rheumatoid arthritis flare. B-cell activation was followed by expansion of circulating CD45-CD31-PDPN+ preinflammatory mesenchymal, or PRIME, cells in the blood from patients with rheumatoid arthritis; these cells shared features of inflammatory synovial fibroblasts. Levels of circulating PRIME cells decreased during flares in all 4 patients, and flow cytometry and sorted-cell RNA-seq confirmed the presence of PRIME cells in 19 additional patients with rheumatoid arthritis. CONCLUSIONS: Longitudinal genomic analysis of rheumatoid arthritis flares revealed PRIME cells in the blood during the period before a flare and suggested a model in which these cells become activated by B cells in the weeks before a flare and subsequently migrate out of the blood into the synovium. (Funded by the National Institutes of Health and others.).
Keywords: Adult; Arthritis, Rheumatoid; B-Lymphocytes; Female; Fibroblasts; Flow Cytometry; Gene Expression; Humans; Male; Mesenchymal Stem Cells; Middle Aged; Patient Acuity; Sequence Analysis, RNA; Surveys and Questionnaires; Symptom Flare Up; Synovial Fluid

Sequential targeted exome sequencing of 1001 patients affected by unexplained limb-girdle weakness. - Topf, Ana; Johnson, Katherine; Bates, Adam; Phillips, Lauren; Chao, Katherine R; England, Eleina M; Laricchia, Kristen M; Mullen, Thomas; Valkanas, Elise; Xu, Liwen; Bertoli, Marta; Blain, Alison; et al. (Genet Med, 2020)
PURPOSE: Several hundred genetic muscle diseases have been described, all of which are rare. Their clinical and genetic heterogeneity means that a genetic diagnosis is challenging. We established an international consortium, MYO-SEQ, to aid the work-ups of muscle disease patients and to better understand disease etiology. METHODS: Exome sequencing was applied to 1001 undiagnosed patients recruited from more than 40 neuromuscular disease referral centers; standardized phenotypic information was collected for each patient. Exomes were examined for variants in 429 genes associated with muscle conditions. RESULTS: We identified suspected pathogenic variants in 52% of patients across 87 genes. We detected 401 novel variants, 116 of which were recurrent. Variants in CAPN3, DYSF, ANO5, DMD, RYR1, TTN, COL6A2, and SGCA collectively accounted for over half of the solved cases; while variants in newer disease genes, such as BVES and POGLUT1, were also found. The remaining well-characterized unsolved patients (48%) need further investigation. CONCLUSION: Using our unique infrastructure, we developed a pathway to expedite muscle disease diagnoses. Our data suggest that exome sequencing should be used for pathogenic variant detection in patients with suspected genetic muscle diseases, focusing first on the most common disease genes described here, and subsequently in rarer and newly characterized disease genes.
Keywords: Anoctamins; Exome; Glucosyltransferases; Humans; Muscular Dystrophies, Limb-Girdle; Whole Exome Sequencing

Serum sphingolipids and incident diabetes in a US population with high diabetes burden: the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). - Chen, Guo-Chong; Chai, Jin Choul; Yu, Bing; Michelotti, Gregory A; Grove, Megan L; Fretts, Amanda M; Daviglus, Martha L; Garcia-Bedoya, Olga L; Thyagarajan, Bharat; Schneiderman, Neil; Cai, Jianwen; Kaplan, Robert C; et al. (Am J Clin Nutr, 2020)
BACKGROUND: Genetic or pharmacological inhibition of de novo sphingolipid synthases prevented diabetes in animal studies. OBJECTIVES: We sought to evaluate prospective associations of serum sphingolipids with incident diabetes in a population-based cohort. METHODS: We included 2010 participants of the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) aged 18-74 y who were free of diabetes and other major chronic diseases at baseline (2008-2011). Metabolomic profiling of fasting serum was performed using a global, untargeted approach. A total of 43 sphingolipids were quantified and, considering subclasses and chemical structures of individual species, 6 sphingolipid scores were constructed. Diabetes status was assessed using standard procedures including blood tests. Multivariable survey Poisson regressions were applied to estimate RR and 95% CI of incident diabetes associated with individual sphingolipids or sphingolipid scores. RESULTS: There were 224 incident cases of diabetes identified during, on average, 6 y of follow-up. After adjustment for socioeconomic and lifestyle factors, a ceramide score (RR Q4 versus Q1 = 2.40; 95% CI: 1.24, 4.65; P-trend = 0.003) and a score of sphingomyelins with fully saturated sphingoid-fatty acid pairs (RR Q4 versus Q1 = 3.15; 95% CI: 1.75, 5.67; P-trend <0.001) both were positively associated with risk of diabetes, whereas scores of glycosylceramides, lactosylceramides, or other unsaturated sphingomyelins (even if having an SFA base) were not associated with risk of diabetes. After additional adjustment for numerous traditional risk factors (especially triglycerides), both associations were attenuated and only the saturated-sphingomyelin score remained associated with risk of diabetes (RR Q4 versus Q1 = 1.98; 95% CI: 1.09, 3.59; P-trend = 0.031). CONCLUSIONS: Our findings suggest that a cluster of saturated sphingomyelins may be associated with elevated risk of diabetes beyond traditional risk factors, which needs to be verified in other population studies. This study was registered at clinicaltrials.gov as NCT02060344.
Keywords: Adolescent; Adult; Aged; Diabetes Mellitus; Female; Hispanic Americans; Humans; Male; Middle Aged; Prospective Studies; Risk Factors; Sphingolipids; United States; Young Adult

Severe neurodevelopmental disease caused by a homozygous TLK2 variant. - Topf, Ana; Oktay, Yavuz; Balaraju, Sunitha; Yilmaz, Elmasnur; Sonmezler, Ece; Yis, Uluc; Laurie, Steven; Thompson, Rachel; Roos, Andreas; MacArthur, Daniel G; Yaramis, Ahmet; Güngör, Serdal; et al. (Eur J Hum Genet, 2020)
A distinct neurodevelopmental phenotype characterised mainly by mild motor and language delay and facial dysmorphism, caused by heterozygous de novo or dominant variants in the TLK2 gene has recently been described. All cases reported carried either truncating variants located throughout the gene, or missense changes principally located at the C-terminal end of the protein mostly resulting in haploinsufficiency of TLK2. Through whole exome sequencing, we identified a homozygous missense variant in TLK2 in a patient showing more severe symptoms than those previously described, including cerebellar vermis hypoplasia and West syndrome. Both parents are heterozygous for the variant and clinically unaffected highlighting that recessive variants in TLK2 can also be disease causing and may act through a different pathomechanism.
Keywords: Adult; Cerebellum; Child; Developmental Disabilities; Female; Heterozygote; Homozygote; Humans; Infant; Male; Mutation, Missense; Nervous System Malformations; Pedigree; Protein Kinases; Spasms, Infantile

Short stature and growth hormone deficiency in a subset of patients with Potocki-Lupski syndrome: Expanding the phenotype of PTLS. - Franciskovich, Rachel; Soler-Alfonso, Claudia; Neira-Fresneda, Juanita; Lupski, James R; McCann-Crosby, Bonnie; Potocki, Lorraine (Am J Med Genet A, 2020)
Potocki-Lupski Syndrome (PTLS, MIM 610883), or duplication of chromosome 17p11.2, is a clinically recognizable condition characterized by infantile hypotonia, failure to thrive, developmental delay, intellectual disability, and congenital anomalies. Short stature, classified as greater than two standard deviations below the mean, has not previously been considered a major feature of PTLS. Retrospective chart review on a cohort of 37 individuals with PTLS was performed to investigate the etiology of short stature. Relevant data included anthropometric measurements, insulin growth factor-1 (IGF-1), insulin-like growth factor binding protein 3 (IGFBP-3), growth hormone (GH) stimulation testing, blood glucose levels, brain MRI, and bone age. Approximately 25% (9/37) of individuals with PTLS had short stature. Growth hormone deficiency (GHD) was definitively identified in two individuals. These two PTLS patients with growth hormone deficiency, as well as three others with short stature and no documented GHD, received growth hormone and obtained improvement in linear growth. One individual was identified to have pituitary abnormalities on MRI and had complications of hypoglycemia due to unrecognized GHD. Individuals with PTLS can benefit from undergoing evaluation for GHD should they present with short stature or hypoglycemia. Early identification of GHD could facilitate potential therapeutic benefit for individuals with PTLS, including linear growth, musculoskeletal, and in cases of hypoglycemia, potentially cognitive development as well.

Spectrum of genetic variants in moderate to severe sporadic hearing loss in Pakistan. - Ramzan, Memoona; Bashir, Rasheeda; Salman, Midhat; Mujtaba, Ghulam; Sobreira, Nara; Witmer, P Dane; Naz, Sadaf (Sci Rep, 2020)
Hearing loss affects 380 million people worldwide due to environmental or genetic causes. Determining the cause of deafness in individuals without previous family history of hearing loss is challenging and has been relatively unexplored in Pakistan. We investigated the spectrum of genetic variants in hearing loss in a cohort of singleton affected individuals born to consanguineous parents. Twenty-one individuals with moderate to severe hearing loss were recruited. We performed whole-exome sequencing on DNA samples from the participants, which identified seventeen variants in ten known deafness genes and one novel candidate gene. All identified variants were homozygous except for two. Eleven of the variants were novel, including one multi-exonic homozygous deletion in OTOA. A missense variant in ESRRB was implicated for recessively inherited moderate to severe hearing loss. Two individuals were heterozygous for variants in MYO7A and CHD7, respectively, consistent with de novo variants or dominant inheritance with incomplete penetrance as the reason for their hearing loss. Our results indicate that similar to familial cases of deafness, variants in a large number of genes are responsible for moderate to severe hearing loss in sporadic individuals born to consanguineous couples.
Keywords: Adolescent; Amino Acid Sequence; Audiometry, Pure-Tone; Child; Child, Preschool; Deafness; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Hearing Loss; Heterozygote; Homozygote; Humans; Mutation, Missense; Pakistan; Phenotype; Whole Exome Sequencing; Young Adult

Spinal muscular atrophy diagnosis and carrier screening from genome sequencing data. - Chen, Xiao; Sanchis-Juan, Alba; French, Courtney E; Connell, Andrew J; Delon, Isabelle; Kingsbury, Zoya; Chawla, Aditi; Halpern, Aaron L; Taft, Ryan J; Bentley, David R; Butchbach, Matthew E R; Raymond, F Lucy; et al. (Genet Med, 2020)
PURPOSE: Spinal muscular atrophy (SMA), caused by loss of the SMN1 gene, is a leading cause of early childhood death. Due to the near identical sequences of SMN1 and SMN2, analysis of this region is challenging. Population-wide SMA screening to quantify the SMN1 copy number (CN) is recommended by the American College of Medical Genetics and Genomics. METHODS: We developed a method that accurately identifies the CN of SMN1 and SMN2 using genome sequencing (GS) data by analyzing read depth and eight informative reference genome differences between SMN1/2. RESULTS: We characterized SMN1/2 in 12,747 genomes, identified 1568 samples with SMN1 gains or losses and 6615 samples with SMN2 gains or losses, and calculated a pan-ethnic carrier frequency of 2%, consistent with previous studies. Additionally, 99.8% of our SMN1 and 99.7% of SMN2 CN calls agreed with orthogonal methods, with a recall of 100% for SMA and 97.8% for carriers, and a precision of 100% for both SMA and carriers. CONCLUSION: This SMN copy-number caller can be used to identify both carrier and affected status of SMA, enabling SMA testing to be offered as a comprehensive test in neonatal care and an accurate carrier screening tool in GS sequencing projects.
Keywords: Base Sequence; Child; Child, Preschool; Humans; Muscular Atrophy, Spinal; Survival of Motor Neuron 1 Protein

Spondyloepimetaphyseal dysplasia with elevated plasma lysosomal enzymes caused by homozygous variant in MBTPS1. - Carvalho, Daniel R; Speck-Martins, Carlos E; Brum, Jaime M; Ferreira, Carlos R; Sobreira, Nara L M (Am J Med Genet A, 2020)
Variants in MBTPS1 (membrane-bound transcription factor peptidase, site 1) encoding the protein convertase site-1 protease (S1P) were recently reported in a single individual with skeletal dysplasia and elevated plasma lysosomal enzymes. Here, we report the second individual with this newly described autosomal recessive spondyloepiphyseal dysplasia (OMIM #618392), presenting severe growth retardation, cataract and dysmorphic features, mainly retromicrognathia. Epilepsy and craniosynostosis were novel findings in our proband. She was found to be homozygous for a novel nonsense variant p.Trp983Ter in MBTPS1. In addition, she had normal levels of lysosomal enzyme activity in leukocytes but elevated levels in plasma. Our description confirms the existence of this new skeletal dysplasia and expands the phenotype and genotype of the disease.
Keywords: Cataract; Child, Preschool; Female; Humans; Lysosomal Storage Diseases; Lysosomes; Pedigree; Phenotype; Proprotein Convertases; Serine Endopeptidases

A structural variation reference for medical and population genetics. - Collins, Ryan L; Brand, Harrison; Karczewski, Konrad J; Zhao, Xuefang; Alföldi, Jessica; Francioli, Laurent C; Khera, Amit V; Lowther, Chelsea; Gauthier, Laura D; Wang, Harold; Watts, Nicholas A; Solomonson, Matthew; et al. (Nature, 2020)
Structural variants (SVs) rearrange large segments of DNA and can have profound consequences in evolution and human disease. As national biobanks, disease-association studies, and clinical genetic testing have grown increasingly reliant on genome sequencing, population references such as the Genome Aggregation Database (gnomAD) have become integral in the interpretation of single-nucleotide variants (SNVs). However, there are no reference maps of SVs from high-coverage genome sequencing comparable to those for SNVs. Here we present a reference of sequence-resolved SVs constructed from 14,891 genomes across diverse global populations (54% non-European) in gnomAD. We discovered a rich and complex landscape of 433,371 SVs, from which we estimate that SVs are responsible for 25-29% of all rare protein-truncating events per genome. We found strong correlations between natural selection against damaging SNVs and rare SVs that disrupt or duplicate protein-coding sequence, which suggests that genes that are highly intolerant to loss-of-function are also sensitive to increased dosage. We also uncovered modest selection against noncoding SVs in cis-regulatory elements, although selection against protein-truncating SVs was stronger than all noncoding effects. Finally, we identified very large (over one megabase), rare SVs in 3.9% of samples, and estimate that 0.13% of individuals may carry an SV that meets the existing criteria for clinically important incidental findings. This SV resource is freely distributed via the gnomAD browser and will have broad utility in population genetics, disease-association studies, and diagnostic screening.
Keywords: Continental Population Groups; Disease; Female; Genetic Testing; Genetic Variation; Genetics, Medical; Genetics, Population; Genome, Human; Genotyping Techniques; Humans; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Reference Standards; Selection, Genetic; Whole Genome Sequencing

Successful treatment of intractable epilepsy with ketogenic diet therapy in twins with ALG3-CDG. - Paketci, C; Edem, P; Hiz, S; Sonmezler, E; Soydemir, D; Sarikaya Uzan, G; Oktay, Y; O'Heir, E; Beltran, S; Laurie, S; Töpf, A; Lochmuller, H; et al. (Brain Dev, 2020)
BACKGROUND: Congenital disorders of glycosylation (CDG) is a heterogeneous group of congenital metabolic diseases with multisystem clinical involvement. ALG3-CDG is a very rare subtype with only 24 cases reported so far. CASE: Here, we report two siblings with dysmorphic features, growth retardation, microcephaly, intractable epilepsy, and hemangioma in the frontal, occipital and lumbosacral regions. RESULTS: We studied two siblings by whole exome sequencing. A pathogenic variant in ALG3 (NM_005787.6: c.165C > T; p.Gly55=) that had been previously associated with congenital glycolysis defect type 1d was identified. Their intractable seizures were controlled by ketogenic diet. CONCLUSION: Although prominent findings of growth retardation and microcephaly seen in our patients have been extensively reported before, presence of hemangioma is a novel finding that may be used as an indication for ALG3-CDG diagnosis. Our patients are the first reported cases whose intractable seizures were controlled with ketogenic diet. This report adds ketogenic diet as an option for treatment of intractable epilepsy in ALG3-CDG.
Keywords: Central Nervous System Neoplasms; Congenital Disorders of Glycosylation; Craniofacial Abnormalities; Developmental Disabilities; Diet, Ketogenic; Drug Resistant Epilepsy; Female; Hemangioma; Humans; Infant; Male; Mannosyltransferases; Twins; Whole Exome Sequencing

Systems Analysis Implicates WAVE2 Complex in the Pathogenesis of Developmental Left-Sided Obstructive Heart Defects. - Edwards, Jonathan J; Rouillard, Andrew D; Fernandez, Nicolas F; Wang, Zichen; Lachmann, Alexander; Shankaran, Sunita S; Bisgrove, Brent W; Demarest, Bradley; Turan, Nahid; Srivastava, Deepak; Bernstein, Daniel; Deanfield, John; et al. (JACC Basic Transl Sci, 2020)
Genetic variants are the primary driver of congenital heart disease (CHD) pathogenesis. However, our ability to identify causative variants is limited. To identify causal CHD genes that are associated with specific molecular functions, the study used prior knowledge to filter de novo variants from 2,881 probands with sporadic severe CHD. This approach enabled the authors to identify an association between left ventricular outflow tract obstruction lesions and genes associated with the WAVE2 complex and regulation of small GTPase-mediated signal transduction. Using CRISPR zebrafish knockdowns, the study confirmed that WAVE2 complex proteins , , and and the regulators of small GTPase signaling and are critical to cardiac development.

TBX6 missense variants expand the mutational spectrum in a non-Mendelian inheritance disease. - Chen, Weisheng; Lin, Jiachen; Wang, Lianlei; Li, Xiaoxin; Zhao, Sen; Liu, Jiaqi; Akdemir, Zeynep C; Zhao, Yanxue; Du, Renqian; Ye, Yongyu; Song, Xiaofei; Zhang, Yuanqiang; et al. (Hum Mutat, 2020)
Congenital scoliosis (CS) is a birth defect with variable clinical and anatomical manifestations due to spinal malformation. The genetic etiology underlying about 10% of CS cases in the Chinese population is compound inheritance by which the gene dosage is reduced below that of haploinsufficiency. In this genetic model, the trait manifests as a result of the combined effect of a rare variant and common pathogenic variant allele at a locus. From exome sequencing (ES) data of 523 patients in Asia and two patients in Texas, we identified six TBX6 gene-disruptive variants from 11 unrelated CS patients via ES and in vitro functional testing. The in trans mild hypomorphic allele was identified in 10 of the 11 subjects; as anticipated these 10 shared a similar spinal deformity of hemivertebrae. The remaining case has a homozygous variant in TBX6 (c.418C>T) and presents a more severe spinal deformity phenotype. We found decreased transcriptional activity and abnormal cellular localization as the molecular mechanisms for TBX6 missense loss-of-function alleles. Expanding the mutational spectrum of TBX6 pathogenic alleles enabled an increased molecular diagnostic detection rate, provided further evidence for the gene dosage-dependent genetic model underlying CS, and refined clinical classification.
Keywords: Alleles; Cell Line; Female; Gene Expression; Genes, Reporter; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Inheritance Patterns; Male; Models, Molecular; Molecular Diagnostic Techniques; Mutation, Missense; Phenotype; Protein Conformation; Radiography; Sequence Analysis, DNA; Spine; Structure-Activity Relationship; T-Box Domain Proteins; Whole Exome Sequencing

A three-year follow-up study evaluating clinical utility of exome sequencing and diagnostic potential of reanalysis. - Fung, Jasmine L F; Yu, Mullin H C; Huang, Shushu; Chung, Claudia C Y; Chan, Marcus C Y; Pajusalu, Sander; Mak, Christopher C Y; Hui, Vivian C C; Tsang, Mandy H Y; Yeung, Kit San; Lek, Monkol; Chung, Brian H Y (NPJ Genom Med, 2020)
Exome sequencing (ES) has become one of the important diagnostic tools in clinical genetics with a reported diagnostic rate of 25-58%. Many studies have illustrated the diagnostic and immediate clinical impact of ES. However, up to 75% of individuals remain undiagnosed and there is scarce evidence supporting clinical utility beyond a follow-up period of >1 year. This is a 3-year follow-up analysis to our previous publication by Mak et al. ( 3:19, 2018), to evaluate the long-term clinical utility of ES and the diagnostic potential of exome reanalysis. The diagnostic yield of the initial study was 41% (43/104). Exome reanalysis in 46 undiagnosed individuals has achieved 12 new diagnoses. The additional yield compared with the initial analysis was at least 12% (increased from 41% to at least 53%). After a median follow-up period of 3.4 years, change in clinical management was observed in 72.2% of the individuals (26/36), leading to positive change in clinical outcome in four individuals (11%). There was a minimum healthcare cost saving of HKD$152,078 (USD$19,497; €17,282) annually for these four individuals. There were a total of six pregnancies from five families within the period. Prenatal diagnosis was performed in four pregnancies; one fetus was affected and resulted in termination. None of the parents underwent preimplantation genetic diagnosis. This 3-year follow-up study demonstrated the long-term clinical utility of ES at individual, familial and health system level, and the promising diagnostic potential of subsequent reanalysis. This highlights the benefits of implementing ES and regular reanalysis in the clinical setting.

Titin Truncating Variants in Adults Without Known Congestive Heart Failure. - Pirruccello, James P; Bick, Alexander; Chaffin, Mark; Aragam, Krishna G; Choi, Seung Hoan; Lubitz, Steven A; Ho, Carolyn Y; Ng, Kenney; Philippakis, Anthony; Ellinor, Patrick T; Kathiresan, Sekar; Khera, Amit V (J Am Coll Cardiol, 2020)
Keywords: Adult; Aged; Asymptomatic Diseases; Connectin; Female; Genetic Variation; Heart Failure; Humans; Male; Middle Aged

Topical cholesterol/lovastatin for the treatment of porokeratosis: A pathogenesis-directed therapy. - Atzmony, Lihi; Lim, Young H; Hamilton, Claire; Leventhal, Jonathan S; Wagner, Annette; Paller, Amy S; Choate, Keith A (J Am Acad Dermatol, 2020)
BACKGROUND: Porokeratosis is associated with mevalonate pathway gene mutations. Therapeutic options are few and often limited in efficacy. We hypothesized that topical therapy that aims to replenish cholesterol, an essential mevalonate pathway end-product, and block the accumulation of mevalonate pathway toxic metabolites could alleviate porokeratosis. OBJECTIVE: To study the efficacy of topical cholesterol/lovastatin in different variants of porokeratosis. METHODS: We enrolled a series of 5 porokeratosis patients,1 with disseminated superficial actinic porokeratosis, 2 with porokeratosis palmaris et plantaris disseminata, and 2 with linear porokeratosis. Patients were genotyped before initiation of therapy. Patients then applied topical cholesterol/lovastatin twice daily to a unilaterally defined treatment area for up to 3 months. The response was evaluated and patients photographed at every visit. RESULTS: Three patients had MVD mutations, and 2 patients had PMVK mutations. Treatment with topical cholesterol/lovastatin (but not cholesterol alone) resulted in near complete clearance of disseminated superficial actinic porokeratosis lesions after 4 weeks of therapy and moderate improvement of porokeratosis palmaris et plantaris disseminata lesions and linear porokeratosis lesions. There were no adverse events. LIMITATIONS: Case series design with a small number of patients. CONCLUSION: Topical cholesterol/lovastatin is an effective and well-tolerated therapy for porokeratosis that underscores the utility of a pathogenesis-based therapy that replaces deficient end products and prevents accumulation of potentially toxic precursors.

Transcriptomic signatures across human tissues identify functional rare genetic variation. - Ferraro, Nicole M; Strober, Benjamin J; Einson, Jonah; Abell, Nathan S; Aguet, Francois; Barbeira, Alvaro N; Brandt, Margot; Bucan, Maja; Castel, Stephane E; Davis, Joe R; Greenwald, Emily; Hess, Gaelen T; et al. (Science, 2020)
Rare genetic variants are abundant across the human genome, and identifying their function and phenotypic impact is a major challenge. Measuring aberrant gene expression has aided in identifying functional, large-effect rare variants (RVs). Here, we expanded detection of genetically driven transcriptome abnormalities by analyzing gene expression, allele-specific expression, and alternative splicing from multitissue RNA-sequencing data, and demonstrate that each signal informs unique classes of RVs. We developed Watershed, a probabilistic model that integrates multiple genomic and transcriptomic signals to predict variant function, validated these predictions in additional cohorts and through experimental assays, and used them to assess RVs in the UK Biobank, the Million Veterans Program, and the Jackson Heart Study. Our results link thousands of RVs to diverse molecular effects and provide evidence to associate RVs affecting the transcriptome with human traits.
Keywords: Genetic Variation; Genome, Human; Humans; Multifactorial Inheritance; Organ Specificity; Transcriptome

truncations cause arrhythmogenic right ventricular cardiomyopathy. - Brun, Francesca; Gigli, Marta; Graw, Sharon L; Judge, Daniel P; Merlo, Marco; Murray, Brittney; Calkins, Hugh; Sinagra, Gianfranco; Taylor, Matthew Rg; Mestroni, Luisa; James, Cynthia A (J Med Genet, 2020)
BACKGROUND: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heart muscle disease that affects predominantly the right ventricle and is part of the spectrum of arrythmogenic cardiomyopathies (ACMs). ARVC is a genetic condition; however, a pathogenic gene variant is found in only half of patients. OBJECTIVE: Filamin C gene truncations () have recently been identified in dilated cardiomyopathy with ventricular arrhythmia and sudden cardiac death, a phenotype partially overlapping with ARVC and part of the ACM spectrum. We hypothesised that could be a novel gene associated with ARVC. METHODS: One hundred fifty-six patients meeting 2010 ARVC Task Force Criteria and lacking variants in known ARVC genes were evaluated for variants. Available family members were tested for cosegregation. RESULTS: We identified two unique variants in two families (c.6565 G>T, p.Glu2189Ter and c.8107delG, p.Asp2703ThrfsTer69), with phenotypes of dominant RV disease fulfilling 'definite' diagnosis of ARVC according to the 2010 Task Force Criteria. Variants in other cardiomyopathy genes were excluded in both kindreds, and segregation analysis revealed that p.Asp2703ThrfsTer69 was a de novo variant. In both families, the disease phenotype was characterised by prominent ventricular arrhythmias and sudden cardiac arrest. CONCLUSION: The identification of as a novel cause of ARVC in two unrelated families expands the spectrum of ARVC disease genes for this disorder. Our findings should prompt inclusion of genetic testing in ARVC to improve diagnostic yield and testing of at-risk relatives in ARVC.
Keywords: Adult; Aged; Arrhythmogenic Right Ventricular Dysplasia; Female; Filamins; Genetic Predisposition to Disease; Genetic Testing; Heart Ventricles; Humans; Male; Middle Aged; Mutation; Phenotype

Two percent lovastatin ointment as a pathogenesis-directed monotherapy for porokeratosis. - Ugwu, Nelson; Choate, Keith A; Atzmony, Lihi (JAAD Case Rep, 2020)

Type 2 and interferon inflammation regulate SARS-CoV-2 entry factor expression in the airway epithelium. - Sajuthi, Satria P; DeFord, Peter; Li, Yingchun; Jackson, Nathan D; Montgomery, Michael T; Everman, Jamie L; Rios, Cydney L; Pruesse, Elmar; Nolin, James D; Plender, Elizabeth G; Wechsler, Michael E; Mak, Angel C Y; et al. (Nat Commun, 2020)
Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2, an emerging virus that utilizes host proteins ACE2 and TMPRSS2 as entry factors. Understanding the factors affecting the pattern and levels of expression of these genes is important for deeper understanding of SARS-CoV-2 tropism and pathogenesis. Here we explore the role of genetics and co-expression networks in regulating these genes in the airway, through the analysis of nasal airway transcriptome data from 695 children. We identify expression quantitative trait loci for both ACE2 and TMPRSS2, that vary in frequency across world populations. We find TMPRSS2 is part of a mucus secretory network, highly upregulated by type 2 (T2) inflammation through the action of interleukin-13, and that the interferon response to respiratory viruses highly upregulates ACE2 expression. IL-13 and virus infection mediated effects on ACE2 expression were also observed at the protein level in the airway epithelium. Finally, we define airway responses to common coronavirus infections in children, finding that these infections generate host responses similar to other viral species, including upregulation of IL6 and ACE2. Our results reveal possible mechanisms influencing SARS-CoV-2 infectivity and COVID-19 clinical outcomes.
Keywords: Angiotensin-Converting Enzyme 2; Betacoronavirus; Child; Coronavirus Infections; COVID-19; Epithelial Cells; Gene Expression Profiling; Gene Expression Regulation; Genetic Variation; Host-Pathogen Interactions; Humans; Inflammation; Interferons; Interleukin-13; Middle Aged; Nasal Mucosa; Pandemics; Peptidyl-Dipeptidase A; Pneumonia, Viral; SARS-CoV-2; Serine Endopeptidases; Virus Internalization

Type 2 and interferon inflammation strongly regulate SARS-CoV-2 related gene expression in the airway epithelium. - Sajuthi, Satria P; DeFord, Peter; Jackson, Nathan D; Montgomery, Michael T; Everman, Jamie L; Rios, Cydney L; Pruesse, Elmar; Nolin, James D; Plender, Elizabeth G; Wechsler, Michael E; Mak, Angel Cy; Eng, Celeste; et al. (bioRxiv, 2020)
Coronavirus disease 2019 (COVID-19) outcomes vary from asymptomatic infection to death. This disparity may reflect different airway levels of the SARS-CoV-2 receptor, ACE2, and the spike protein activator, TMPRSS2. Here we explore the role of genetics and co-expression networks in regulating these genes in the airway, through the analysis of nasal airway transcriptome data from 695 children. We identify expression quantitative trait loci (eQTL) for both and , that vary in frequency across world populations. Importantly, we find is part of a mucus secretory network, highly upregulated by T2 inflammation through the action of interleukin-13, and that interferon response to respiratory viruses highly upregulates expression. Finally, we define airway responses to coronavirus infections in children, finding that these infections upregulate while also stimulating a more pronounced cytotoxic immune response relative to other respiratory viruses. Our results reveal mechanisms likely influencing SARS-CoV-2 infectivity and COVID-19 clinical outcomes.

Tyrosyl phosphorylation of PZR promotes hypertrophic cardiomyopathy in PTPN11-associated Noonan syndrome with multiple lentigines. - Yi, Jae-Sung; Perla, Sravan; Enyenihi, Liz; Bennett, Anton M (JCI Insight, 2020)
Noonan syndrome with multiple lentigines (NSML) is a rare autosomal dominant disorder that presents with cardio-cutaneous-craniofacial defects. Hypertrophic cardiomyopathy (HCM) represents the major life-threatening presentation in NSML. Mutations in the PTPN11 gene that encodes for the protein tyrosine phosphatase (PTP), SHP2, represents the predominant cause of HCM in NSML. NSML-associated PTPN11 mutations render SHP2 catalytically inactive with an "open" conformation. NSML-associated PTPN11 mutations cause hypertyrosyl phosphorylation of the transmembrane glycoprotein, protein zero-related (PZR), resulting in increased SHP2 binding. Here we show that NSML mice harboring a tyrosyl phosphorylation-defective mutant of PZR (NSML/PZRY242F) that is defective for SHP2 binding fail to develop HCM. Enhanced AKT/S6 kinase signaling in heart lysates of NSML mice was reversed in NSML/PZRY242F mice, demonstrating that PZR/SHP2 interactions promote aberrant AKT/S6 kinase activity in NSML. Enhanced PZR tyrosyl phosphorylation in the hearts of NSML mice was found to drive myocardial fibrosis by engaging an Src/NF-κB pathway, resulting in increased activation of IL-6. Increased expression of IL-6 in the hearts of NSML mice was reversed in NSML/PZRY242F mice, and PZRY242F mutant fibroblasts were defective for IL-6 secretion and STAT3-mediated fibrogenesis. These results demonstrate that NSML-associated PTPN11 mutations that induce PZR hypertyrosyl phosphorylation trigger pathophysiological signaling that promotes HCM and cardiac fibrosis.
Keywords: Animals; Cardiomyopathy, Hypertrophic; Disease Models, Animal; Female; Intracellular Signaling Peptides and Proteins; LEOPARD Syndrome; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Myocytes, Cardiac; Phosphoproteins; Phosphorylation; Protein Tyrosine Phosphatase, Non-Receptor Type 11; Tyrosine

Using to drive the diagnosis and understand the mechanisms of rare human diseases. - Link, Nichole; Bellen, Hugo J (Development, 2020)
Next-generation sequencing has greatly accelerated the discovery of rare human genetic diseases. Nearly 45% of patients have variants associated with known diseases but the unsolved cases remain a conundrum. Moreover, causative mutations can be difficult to pinpoint because variants frequently map to genes with no previous disease associations and, often, only one or a few patients with variants in the same gene are identified. Model organisms, such as , can help to identify and characterize these new disease-causing genes. Importantly, allow quick and sophisticated genetic manipulations, permit functional testing of human variants, enable the characterization of pathogenic mechanisms and are amenable to drug tests. In this Spotlight, focusing on microcephaly as a case study, we highlight how studies of human genes in have aided our understanding of human genetic disorders, allowing the identification of new genes in well-established signaling pathways.
Keywords: Animals; Disease Models, Animal; Drosophila melanogaster; Genetic Techniques; Human Genetics; Humans; Microcephaly; Rare Diseases

The utility of exome sequencing for fetal pleural effusions. - Jelin, Angie C; Sobreira, Nara; Wohler, Elizabeth; Solomon, Benjamin; Sparks, Teresa; Sagaser, Katelynn G; Forster, Katherine R; Miller, Jena; Witmer, P Dane; Hamosh, Ada; Valle, David; Blakemore, Karin (Prenat Diagn, 2020)
OBJECTIVE: We sought to evaluate the performance of exome sequencing (ES) in determining an underlying genetic etiology for cases of fetal pleural effusions. STUDY DESIGN: We examined a prospective cohort series of fetal pleural effusions visualized sonographically between 1 April 2016 and 31 August 2017. Fetal pleural effusions attributed to twin sharing, anemia, or structural anomalies were excluded, as were all cases with a genetic diagnosis established by karyotype or chromosomal microarray analysis. The remaining cases with pleural effusions of unclear etiology were offered ES. ES was performed by clinical sequencing and/or sequencing under the Baylor-Hopkins Center for Mendelian Genomics' (BHCMG) research platform. All cases were evaluated for novel genes or phenotypic expansion of disease-causing genes. RESULTS: ES was performed on six probands affected by pleural effusions. A pathogenic variant was identified in one case (16.7%). Four additional cases had variants of uncertain significance (VUS) in candidate genes of pathological interest. Neither clinical nor candidate genes were evident in the final case. CONCLUSION: ES should be considered in the evaluation of prenatally detected idiopathic pleural effusions when other diagnostic workup for a genetic etiology has failed.

Validation of a Genome-Wide Polygenic Score for Coronary Artery Disease in South Asians. - Wang, Minxian; Menon, Ramesh; Mishra, Sanghamitra; Patel, Aniruddh P; Chaffin, Mark; Tanneeru, Deepak; Deshmukh, Manjari; Mathew, Oshin; Apte, Sanika; Devanboo, Christina S; Sundaram, Sumathi; Lakshmipathy, Praveena; et al. (J Am Coll Cardiol, 2020)
BACKGROUND: Genome-wide polygenic scores (GPS) integrate information from many common DNA variants into a single number. Because rates of coronary artery disease (CAD) are substantially higher among South Asians, a GPS to identify high-risk individuals may be particularly useful in this population. OBJECTIVES: This analysis used summary statistics from a prior genome-wide association study to derive a new GPS for South Asians. METHODS: This GPS was validated in 7,244 South Asian UK Biobank participants and tested in 491 individuals from a case-control study in Bangladesh. Next, a static ancestry and GPS reference distribution was built using whole-genome sequencing from 1,522 Indian individuals, and a framework was tested for projecting individuals onto this static ancestry and GPS reference distribution using 1,800 CAD cases and 1,163 control subjects newly recruited in India. RESULTS: The GPS, containing 6,630,150 common DNA variants, had an odds ratio (OR) per SD of 1.58 in South Asian UK Biobank participants and 1.60 in the Bangladeshi study (p < 0.001 for each). Next, individuals of the Indian case-control study were projected onto static reference distributions, observing an OR/SD of 1.66 (p < 0.001). Compared with the middle quintile, risk for CAD was most pronounced for those in the top 5% of the GPS distribution-ORs of 4.16, 2.46, and 3.22 in the South Asian UK Biobank, Bangladeshi, and Indian studies, respectively (p < 0.05 for each). CONCLUSIONS: The new GPS has been developed and tested using 3 distinct South Asian studies, and provides a generalizable framework for ancestry-specific GPS assessment.
Keywords: Adult; Aged; Bangladesh; Case-Control Studies; Coronary Artery Disease; Female; Genome-Wide Association Study; Humans; India; Male; Middle Aged; Multifactorial Inheritance

A variant-centric perspective on geographic patterns of human allele frequency variation. - Biddanda, Arjun; Rice, Daniel P; Novembre, John (Elife, 2020)
A key challenge in human genetics is to understand the geographic distribution of human genetic variation. Often genetic variation is described by showing relationships among populations or individuals, drawing inferences over many variants. Here, we introduce an alternative representation of genetic variation that reveals the relative abundance of different allele frequency patterns. This approach allows viewers to easily see several features of human genetic structure: (1) most variants are rare and geographically localized, (2) variants that are common in a single geographic region are more likely to be shared across the globe than to be private to that region, and (3) where two individuals differ, it is most often due to variants that are found globally, regardless of whether the individuals are from the same region or different regions. Our variant-centric visualization clarifies the geographic patterns of human variation and can help address misconceptions about genetic differentiation among populations.
Keywords: Gene Frequency; Genetic Variation; Genetics, Population; Geography; Humans

variants are associated with multiple congenital anomalies including ciliopathy phenotypes. - Marquez, Jonathan; Mann, Nina; Arana, Kathya; Deniz, Engin; Ji, Weizhen; Konstantino, Monica; Mis, Emily K; Deshpande, Charu; Jeffries, Lauren; McGlynn, Julie; Hugo, Hannah; Widmeier, Eugen; et al. (J Med Genet, 2020)
BACKGROUND: Cilia are dynamic cellular extensions that generate and sense signals to orchestrate proper development and tissue homeostasis. They rely on the underlying polarisation of cells to participate in signalling. Cilia dysfunction is a well-known cause of several diseases that affect multiple organ systems including the kidneys, brain, heart, respiratory tract, skeleton and retina. METHODS: Among individuals from four unrelated families, we identified variants in ( that manifested in a variety of pathologies. In our proband, we also examined patient tissues. We depleted in frog embryos to generate a loss-of-function model. Finally, we tested the pathogenicity of patient variants through rescue experiments in the frog model. RESULTS: Patients with variants of were found to have a variety of phenotypes including cystic kidneys, nephrotic syndrome, hydrocephalus, limb abnormalities, congenital heart disease and craniofacial malformations. We also observed a loss of cilia in cystic kidney tissue of our proband. Knockdown of in embryos recapitulated many of these phenotypes and resulted in a loss of cilia in multiple tissues. Unlike introduction of wildtype in frog embryos depleted of introduction of patient variants was largely ineffective in restoring proper ciliation and tissue morphology in the kidney and brain suggesting that the variants were indeed detrimental to function. CONCLUSION: These findings in both patient tissues and shed light on how mutations in may lead to tissue-specific manifestations of disease. DLG5 is essential for cilia and many of the patient phenotypes are in the ciliopathy spectrum.

Variants in CAPZA2, a member of an F-actin capping complex, cause intellectual disability and developmental delay. - Huang, Yan; Mao, Xiao; van Jaarsveld, Richard H; Shu, Li; Terhal, Paulien A; Jia, Zhengjun; Xi, Hui; Peng, Ying; Yan, Huiming; Yuan, Shan; Li, Qibin; Wang, Hua; et al. (Hum Mol Genet, 2020)
The actin cytoskeleton is regulated by many proteins including capping proteins that stabilize actin filaments (F-actin) by inhibiting actin polymerization and depolymerization. Here, we report two pediatric probands who carry damaging heterozygous de novo mutations in CAPZA2 (HGNC: 1490) and exhibit neurological symptoms with shared phenotypes including global motor development delay, speech delay, intellectual disability, hypotonia and a history of seizures. CAPZA2 encodes a subunit of an F-actin-capping protein complex (CapZ). CapZ is an obligate heterodimer consisting of α and β heterodimer conserved from yeast to human. Vertebrate genomes contain three α subunits encoded by three different genes and CAPZA2 encodes the α2 subunit. The single orthologue of CAPZA genes in Drosophila is cpa. Loss of cpa leads to lethality in early development and expression of the human reference; CAPZA2 rescues this lethality. However, the two CAPZA2 variants identified in the probands rescue this lethality at lower efficiency than the reference. Moreover, expression of the CAPZA2 variants affects bristle morphogenesis, a process that requires extensive actin polymerization and bundling during development. Taken together, our findings suggest that variants in CAPZA2 lead to a non-syndromic neurodevelopmental disorder in children.

A vast resource of allelic expression data spanning human tissues. - Castel, Stephane E; Aguet, Francois; Mohammadi, Pejman; Ardlie, Kristin G; Lappalainen, Tuuli (Genome Biol, 2020)
Allele expression (AE) analysis robustly measures cis-regulatory effects. Here, we present and demonstrate the utility of a vast AE resource generated from the GTEx v8 release, containing 15,253 samples spanning 54 human tissues for a total of 431 million measurements of AE at the SNP level and 153 million measurements at the haplotype level. In addition, we develop an extension of our tool phASER that allows effect sizes of cis-regulatory variants to be estimated using haplotype-level AE data. This AE resource is the largest to date, and we are able to make haplotype-level data publicly available. We anticipate that the availability of this resource will enable future studies of regulatory variation across human tissues.

What Is Familial Hypercholesterolemia, and Why Does It Matter? - Khera, Amit V; Hegele, Robert A (Circulation, 2020)
Keywords: Atherosclerosis; Cardiovascular Diseases; Cholesterol, LDL; Humans; Hyperlipoproteinemia Type II; Prevalence

Whole exome sequencing identified ATP6V1C2 as a novel candidate gene for recessive distal renal tubular acidosis. - Jobst-Schwan, Tilman; Klämbt, Verena; Tarsio, Maureen; Heneghan, John F; Majmundar, Amar J; Shril, Shirlee; Buerger, Florian; Ottlewski, Isabel; Shmukler, Boris E; Topaloglu, Rezan; Hashmi, Seema; Hafeez, Farkhanda; et al. (Kidney Int, 2020)
Distal renal tubular acidosis is a rare renal tubular disorder characterized by hyperchloremic metabolic acidosis and impaired urinary acidification. Mutations in three genes (ATP6V0A4, ATP6V1B1 and SLC4A1) constitute a monogenic causation in 58-70% of familial cases of distal renal tubular acidosis. Recently, mutations in FOXI1 have been identified as an additional cause. Therefore, we hypothesized that further monogenic causes of distal renal tubular acidosis remain to be discovered. Panel sequencing and/or whole exome sequencing was performed in a cohort of 17 families with 19 affected individuals with pediatric onset distal renal tubular acidosis. A causative mutation was detected in one of the three "classical" known distal renal tubular acidosis genes in 10 of 17 families. The seven unsolved families were then subjected to candidate whole exome sequencing analysis. Potential disease causing mutations in three genes were detected: ATP6V1C2, which encodes another kidney specific subunit of the V-type proton ATPase (1 family); WDR72 (2 families), previously implicated in V-ATPase trafficking in cells; and SLC4A2 (1 family), a paralog of the known distal renal tubular acidosis gene SLC4A1. Two of these mutations were assessed for deleteriousness through functional studies. Yeast growth assays for ATP6V1C2 revealed loss-of-function for the patient mutation, strongly supporting ATP6V1C2 as a novel distal renal tubular acidosis gene. Thus, we provided a molecular diagnosis in a known distal renal tubular acidosis gene in 10 of 17 families (59%) with this disease, identified mutations in ATP6V1C2 as a novel human candidate gene, and provided further evidence for phenotypic expansion in WDR72 mutations from amelogenesis imperfecta to distal renal tubular acidosis.

Whole exome sequencing in a large pedigree with DCM identifies a novel mutation in . - Robyns, Tomas; Willems, Rik; Van Cleemput, Johan; Jhangiani, Shalini; Muzny, Donna; Gibbs, Richard; Lupski, James R; Breckpot, Jeroen; Devriendt, Koenraad; Corveleyn, Anniek (Acta Cardiol, 2020)
Familial dilated cardiomyopathy (DCM) is genetically heterogeneous and is associated with mutations in at least 40 different genes. Apart from encoding the giant protein Titin, none of these genes have an expected diagnostic yield of more than 5% complicating genetic diagnosis. Whole exome sequencing (WES) is a powerful alternative for the identification of the causal gene, however variant interpretation remains challenging. We report on WES in a large family with autosomal dominant DCM complicated by end stage heart failure and non-sustained ventricular arrhythmias in whom no causative mutation was identified using a targeted gene panel including 28 genes. WES was applied on 2 affected cousins. Stringent filtering of the identified genetic variants was performed including population variant frequencies, in silico analysis, orthologous and paralogous conservation. Subsequently Sanger sequencing was performed for 10 potential disease causing variants in order to confirm the presence of the variant and to evaluate co-segregation. Only one variant in exon 9 of the RBM20 gene (c.2714T > A, p.Met950Lys, NM_001334363) showed full co-segregation in the 7 affected family members resulting in a maximum 2-point LOD score of 2.1 and suggesting this as the pathogenic mutation responsible for the phenotype. Recently mutations in RBM20 have been linked to arrhythmogenic dilated cardiomyopathy caused by defective splicing of the giant sarcomere protein titin and abnormal calcium handling. We report the identification of a novel mutation in RBM20 by WES in a large pedigree with DCM.

Whole-exome sequencing in adult patients with developmental and epileptic encephalopathy: It is never too late. - Minardi, Raffaella; Licchetta, Laura; Baroni, Maria Chiara; Pippucci, Tommaso; Stipa, Carlotta; Mostacci, Barbara; Severi, Giulia; Toni, Francesco; Bergonzini, Luca; Carelli, Valerio; Seri, Marco; Tinuper, Paolo; et al. (Clin Genet, 2020)
Developmental and epileptic encephalopathies (DEE) encompass rare, sporadic neurodevelopmental disorders and usually with pediatric onset. As these conditions are characterized by marked clinical and genetic heterogeneity, whole-exome sequencing (WES) represents the strategy of choice for the molecular diagnosis. While its usefulness is well established in pediatric DEE cohorts, our study is aimed at assessing the WES feasibility in adult DEE patients who experienced a diagnostic odyssey prior to the advent of this technique. We analyzed exomes from 71 unrelated adult DEE patients, consecutively recruited from an Italian cohort for the EPI25 Project. All patients underwent accurate clinical and electrophysiological characterization. An overwhelming percentage (90.1%) had already undergone negative genetic testing. Variants were classified according to the American College of Medical Genetics and Genomics guidelines. WES disclosed 24 (likely) pathogenic variants among 18 patients in epilepsy-related genes with either autosomal dominant, recessive or X-linked inheritance. Ten of these were novel. We obtained a diagnostic yield of 25.3%, higher among patients with brain malformations, early-onset epilepsy and dysmorphisms. Despite a median diagnostic delay of 38.7 years, WES analysis provided the long-awaited diagnosis for 18 adult patients, which also had an impact on the clinical management of 50% of them.

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Whole Exome Sequencing; Wolff-Parkinson-White Syndrome; Young Adult

X-chromosome association studies of congenital heart defects. - Agopian, A J; Hoang, Thanh T; Goldmuntz, Elizabeth; Hakonarson, Hakon; Musfee, Fadi I; Mitchell, Laura E (Am J Med Genet A, 2020)
Keywords: Chromosome Deletion; Chromosomes, Human, X; Female; Genes, X-Linked; Genetic Association Studies; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Male

Xq22 deletions and correlation with distinct neurological disease traits in females: Further evidence for a contiguous gene syndrome. - Hijazi, Hadia; Coelho, Fernanda S; Gonzaga-Jauregui, Claudia; Bernardini, Laura; Mar, Soe S; Manning, Melanie A; Hanson-Kahn, Andrea; Naidu, Sakkubai; Srivastava, Siddharth; Lee, Jennifer A; Jones, Julie R; Friez, Michael J; et al. (Hum Mutat, 2020)
Xq22 deletions that encompass PLP1 (Xq22-PLP1-DEL) are notable for variable expressivity of neurological disease traits in females ranging from a mild late-onset form of spastic paraplegia type 2 (MIM# 312920), sometimes associated with skewed X-inactivation, to an early-onset neurological disease trait (EONDT) of severe developmental delay, intellectual disability, and behavioral abnormalities. Size and gene content of Xq22-PLP1-DEL vary and were proposed as potential molecular etiologies underlying variable expressivity in carrier females where two smallest regions of overlap (SROs) were suggested to influence disease. We ascertained a cohort of eight unrelated patients harboring Xq22-PLP1-DEL and performed high-density array comparative genomic hybridization and breakpoint-junction sequencing. Molecular characterization of Xq22-PLP1-DEL from 17 cases (eight herein and nine published) revealed an overrepresentation of breakpoints that reside within repeats (11/17, ~65%) and the clustering of ~47% of proximal breakpoints in a genomic instability hotspot with characteristic non-B DNA density. These findings implicate a potential role for genomic architecture in stimulating the formation of Xq22-PLP1-DEL. The correlation of Xq22-PLP1-DEL gene content with neurological disease trait in female cases enabled refinement of the associated SROs to a single genomic interval containing six genes. Our data support the hypothesis that genes contiguous to PLP1 contribute to EONDT.
Keywords: Child; Child, Preschool; Chromosome Breakpoints; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, X; Comparative Genomic Hybridization; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Nervous System Diseases; Pedigree; Phenotype; Quantitative Trait, Heritable; Repetitive Sequences, Nucleic Acid; Sex Factors; Syndrome; X Chromosome Inactivation

A2ML1 and otitis media: novel variants, differential expression, and relevant pathways. - Larson, Eric D; Magno, Jose Pedrito M; Steritz, Matthew J; Llanes, Erasmo Gonzalo D V; Cardwell, Jonathan; Pedro, Melquiadesa; Roberts, Tori Bootpetch; Einarsdottir, Elisabet; Rosanes, Rose Anne Q; Greenlee, Christopher; Santos, Rachel Ann P; Yousaf, Ayesha; et al. (Hum Mutat, 2019)
A genetic basis for otitis media is established, however, the role of rare variants in disease etiology is largely unknown. Previously a duplication variant within A2ML1 was identified as a significant risk factor for otitis media in an indigenous Filipino population and in US children. In this report exome and Sanger sequencing was performed using DNA samples from the indigenous Filipino population, Filipino cochlear implantees, US probands, Finnish, and Pakistani families with otitis media. Sixteen novel, damaging A2ML1 variants identified in otitis media patients were rare or low-frequency in population-matched controls. In the indigenous population, both gingivitis and A2ML1 variants including the known duplication variant and the novel splice variant c.4061 + 1 G>C were independently associated with otitis media. Sequencing of salivary RNA samples from indigenous Filipinos demonstrated lower A2ML1 expression according to the carriage of A2ML1 variants. Sequencing of additional salivary RNA samples from US patients with otitis media revealed differentially expressed genes that are highly correlated with A2ML1 expression levels. In particular, RND3 is upregulated in both A2ML1 variant carriers and high-A2ML1 expressors. These findings support a role for A2ML1 in keratinocyte differentiation within the middle ear as part of otitis media pathology and the potential application of ROCK inhibition in otitis media.

Aberrant Function of the C-Terminal Tail of HIST1H1E Accelerates Cellular Senescence and Causes Premature Aging. - Flex, Elisabetta; Martinelli, Simone; Van Dijck, Anke; Ciolfi, Andrea; Cecchetti, Serena; Coluzzi, Elisa; Pannone, Luca; Andreoli, Cristina; Radio, Francesca Clementina; Pizzi, Simone; Carpentieri, Giovanna; Bruselles, Alessandro; et al. (Am J Hum Genet, 2019)
Histones mediate dynamic packaging of nuclear DNA in chromatin, a process that is precisely controlled to guarantee efficient compaction of the genome and proper chromosomal segregation during cell division and to accomplish DNA replication, transcription, and repair. Due to the important structural and regulatory roles played by histones, it is not surprising that histone functional dysregulation or aberrant levels of histones can have severe consequences for multiple cellular processes and ultimately might affect development or contribute to cell transformation. Recently, germline frameshift mutations involving the C-terminal tail of HIST1H1E, which is a widely expressed member of the linker histone family and facilitates higher-order chromatin folding, have been causally linked to an as-yet poorly defined syndrome that includes intellectual disability. We report that these mutations result in stable proteins that reside in the nucleus, bind to chromatin, disrupt proper compaction of DNA, and are associated with a specific methylation pattern. Cells expressing these mutant proteins have a dramatically reduced proliferation rate and competence, hardly enter into the S phase, and undergo accelerated senescence. Remarkably, clinical assessment of a relatively large cohort of subjects sharing these mutations revealed a premature aging phenotype as a previously unrecognized feature of the disorder. Our findings identify a direct link between aberrant chromatin remodeling, cellular senescence, and accelerated aging.

ACTN2 mutations cause "Multiple structured Core Disease" (MsCD). - Lornage, Xavière; Romero, Norma B; Grosgogeat, Claire A; Malfatti, Edoardo; Donkervoort, Sandra; Marchetti, Michael M; Neuhaus, Sarah B; Foley, A Reghan; Labasse, Clémence; Schneider, Raphaël; Carlier, Robert Y; Chao, Katherine R; et al. (Acta Neuropathol, 2019)
The identification of genes implicated in myopathies is essential for diagnosis and for revealing novel therapeutic targets. Here we characterize a novel subclass of congenital myopathy at the morphological, molecular, and functional level. Through exome sequencing, we identified de novo ACTN2 mutations, a missense and a deletion, in two unrelated patients presenting with progressive early-onset muscle weakness and respiratory involvement. Morphological and ultrastructural analyses of muscle biopsies revealed a distinctive pattern with the presence of muscle fibers containing small structured cores and jagged Z-lines. Deeper analysis of the missense mutation revealed mutant alpha-actinin-2 properly localized to the Z-line in differentiating myotubes and its level was not altered in muscle biopsy. Modelling of the disease in zebrafish and mice by exogenous expression of mutated alpha-actinin-2 recapitulated the abnormal muscle function and structure seen in the patients. Motor deficits were noted in zebrafish, and muscle force was impaired in isolated muscles from AAV-transduced mice. In both models, sarcomeric disorganization was evident, while expression of wild-type alpha-actinin-2 did not result in muscle anomalies. The murine muscles injected with mutant ACTN2 displayed cores and Z-line defects. Dominant ACTN2 mutations were previously associated with cardiomyopathies, and our data demonstrate that specific mutations in the well-known Z-line regulator alpha-actinin-2 can cause a skeletal muscle disorder.

Allele-specific RNA interference prevents neuropathy in Charcot-Marie-Tooth disease type 2D mouse models. - Morelli, Kathryn H; Griffin, Laurie B; Pyne, Nettie K; Wallace, Lindsay M; Fowler, Allison M; Oprescu, Stephanie N; Takase, Ryuichi; Wei, Na; Meyer-Schuman, Rebecca; Mellacheruvu, Dattatreya; Kitzman, Jacob O; Kocen, Samuel G; et al. (J Clin Invest, 2019)
Gene therapy approaches are being deployed to treat recessive genetic disorders by restoring the expression of mutated genes. However, the feasibility of these approaches for dominantly inherited diseases - where treatment may require reduction in the expression of a toxic mutant protein resulting from a gain-of-function allele - is unclear. Here we show the efficacy of allele-specific RNAi as a potential therapy for Charcot-Marie-Tooth disease type 2D (CMT2D), caused by dominant mutations in glycyl-tRNA synthetase (GARS). A de novo mutation in GARS was identified in a patient with a severe peripheral neuropathy, and a mouse model precisely recreating the mutation was produced. These mice developed a neuropathy by 3-4 weeks of age, validating the pathogenicity of the mutation. RNAi sequences targeting mutant GARS mRNA, but not wild-type, were optimized and then packaged into AAV9 for in vivo delivery. This almost completely prevented the neuropathy in mice treated at birth. Delaying treatment until after disease onset showed modest benefit, though this effect decreased the longer treatment was delayed. These outcomes were reproduced in a second mouse model of CMT2D using a vector specifically targeting that allele. The effects were dose dependent, and persisted for at least 1 year. Our findings demonstrate the feasibility of AAV9-mediated allele-specific knockdown and provide proof of concept for gene therapy approaches for dominant neuromuscular diseases.

Apparent Acetaminophen Toxicity in a Patient with Transaldolase Deficiency. - Lee-Barber, Jasmine; English, Taylor E; Britton, Jacquelyn F; Sobreira, Nara; Goldstein, Jason; Valle, David; Bjornsson, Hans Tomas (JIMD Rep, 2019)
Transaldolase deficiency (MIM#: 606003) is a rare autosomal recessive defect in the pentose phosphate pathway. Affected individuals are at risk for progressive liver failure and hepatocarcinoma. In the transaldolase-deficient mouse model (Taldo1 ), these hepatic complications are accentuated by oxidative stress related to acetaminophen administration. We report a 13-month-old transaldolase-deficient male who developed mild liver failure after receiving standard doses of acetaminophen during a febrile respiratory syncytial virus infection. He was admitted for respiratory distress with neutropenia and thrombocytopenia, but developed an enlarged nodular liver with accompanying splenomegaly and rising alpha-fetoprotein which peaked 2 weeks after acetaminophen exposure. Whole exome sequencing revealed compound heterozygous variants c.512_514delCCT (p.Ser171del) and c.931G > T (p.Gly311Trp) in TALDO1 (HGNC:11559), which encodes transaldolase (EC 2.2.1.2), a key enzyme in ribose metabolism. Urine polyols and plasma metabolomics confirmed the diagnosis of transaldolase deficiency. Studies on the Taldo1 mouse model demonstrate acetaminophen-induced liver failure can be prevented by administration of the antioxidant N-acetylcysteine. Moreover, a published report showed treatment of a transaldolase-deficient patient with N-acetylcysteine was associated with a decrease in alpha-fetoprotein levels. After discontinuation of acetaminophen and prior to initiation of N-acetylcysteine treatment, our patient demonstrated resolving alpha-fetoprotein levels suggesting acetaminophen incited the liver failure. Conclusion: Our observations support the conclusion from mouse model studies that transaldolase-deficient patients are uniquely sensitive to acetaminophen and should avoid this antipyretic. Recognition of this individualized toxicity and avoidance of acetaminophen are essential for management of these patients.

Atlas-CNV: a validated approach to call single-exon CNVs in the eMERGESeq gene panel. - Chiang, Theodore; Liu, Xiuping; Wu, Tsung-Jung; Hu, Jianhong; Sedlazeck, Fritz J; White, Simon; Schaid, Daniel; Andrade, Mariza de; Jarvik, Gail P; Crosslin, David; Stanaway, Ian; Carrell, David S; et al. (Genet Med, 2019)
PURPOSE: To provide a validated method to confidently identify exon-containing copy-number variants (CNVs), with a low false discovery rate (FDR), in targeted sequencing data from a clinical laboratory with particular focus on single-exon CNVs. METHODS: DNA sequence coverage data are normalized within each sample and subsequently exonic CNVs are identified in a batch of samples, when the target log ratio of the sample to the batch median exceeds defined thresholds. The quality of exonic CNV calls is assessed by C-scores (Z-like scores) using thresholds derived from gold standard samples and simulation studies. We integrate an ExonQC threshold to lower FDR and compare performance with alternate software (VisCap). RESULTS: Thirteen CNVs were used as a truth set to validate Atlas-CNV and compared with VisCap. We demonstrated FDR reduction in validation, simulation, and 10,926 eMERGESeq samples without sensitivity loss. Sixty-four multiexon and 29 single-exon CNVs with high C-scores were assessed by Multiplex Ligation-dependent Probe Amplification (MLPA). CONCLUSION: Atlas-CNV is validated as a method to identify exonic CNVs in targeted sequencing data generated in the clinical laboratory. The ExonQC and C-score assignment can reduce FDR (identification of targets with high variance) and improve calling accuracy of single-exon CNVs respectively. We propose guidelines and criteria to identify high confidence single-exon CNVs.

Biallelic and De Novo Variants in DONSON Reveal a Clinical Spectrum of Cell Cycle-opathies with Microcephaly, Dwarfism and Skeletal Abnormalities. - Karaca, Ender; Posey, Jennifer E; Bostwick, Bret; Liu, Pengfei; Gezdirici, Alper; Yesil, Gözde; Coban Akdemir, Zeynep; Bayram, Yavuz; Harms, Frederike L; Meinecke, Peter; Alawi, Malik; Bacino, Carlos A; et al. (Am J Med Genet A, 2019)
Co-occurrence of primordial dwarfism and microcephaly together with particular skeletal findings are seen in a wide range of Mendelian syndromes including microcephaly micromelia syndrome (MMS, OMIM 251230), microcephaly, short stature, and limb abnormalities (MISSLA, OMIM 617604), and microcephalic primordial dwarfisms (MPDs). Genes associated with these syndromes encode proteins that have crucial roles in DNA replication or in other critical steps of the cell cycle that link DNA replication to cell division. We identified four unrelated families with five affected individuals having biallelic or de novo variants in DONSON presenting with a core phenotype of severe short stature (z score < -3 SD), additional skeletal abnormalities, and microcephaly. Two apparently unrelated families with identical homozygous c.631C > T p.(Arg211Cys) variant had clinical features typical of Meier-Gorlin syndrome (MGS), while two siblings with compound heterozygous c.346delG p.(Asp116Ile*62) and c.1349A > G p.(Lys450Arg) variants presented with Seckel-like phenotype. We also identified a de novo c.683G > T p.(Trp228Leu) variant in DONSON in a patient with prominent micrognathia, short stature and hypoplastic femur and tibia, clinically diagnosed with Femoral-Facial syndrome (FFS, OMIM 134780). Biallelic variants in DONSON have been recently described in individuals with microcephalic dwarfism. These studies also demonstrated that DONSON has an essential conserved role in the cell cycle. Here we describe novel biallelic and de novo variants that are associated with MGS, Seckel-like phenotype and FFS, the last of which has not been associated with any disease gene to date.

Biallelic CACNA2D2 variants in epileptic encephalopathy and cerebellar atrophy. - Punetha, Jaya; Karaca, Ender; Gezdirici, Alper; Lamont, Ryan E; Pehlivan, Davut; Marafi, Dana; Appendino, Juan P; Hunter, Jill V; Akdemir, Zeynep C; Fatih, Jawid M; Jhangiani, Shalini N; Gibbs, Richard A; et al. (Ann Clin Transl Neurol, 2019)
OBJECTIVE: To characterize the molecular and clinical phenotypic basis of developmental and epileptic encephalopathies caused by rare biallelic variants in CACNA2D2. METHODS: Two affected individuals from a family with clinical features of early onset epileptic encephalopathy were recruited for exome sequencing at the Centers for Mendelian Genomics to identify their molecular diagnosis. GeneMatcher facilitated identification of a second family with a shared candidate disease gene identified through clinical gene panel-based testing. RESULTS: Rare biallelic CACNA2D2 variants have been previously reported in three families with developmental and epileptic encephalopathy, and one family with congenital ataxia. We identified three individuals in two unrelated families with novel homozygous rare variants in CACNA2D2 with clinical features of developmental and epileptic encephalopathy and cerebellar atrophy. Family 1 includes two affected siblings with a likely damaging homozygous rare missense variant c.1778G>C; p.(Arg593Pro) in CACNA2D2. Family 2 includes a proband with a homozygous rare nonsense variant c.485_486del; p.(Tyr162Ter) in CACNA2D2. We compared clinical and molecular findings from all nine individuals reported to date and note that cerebellar atrophy is shared among all. INTERPRETATION: Our study supports the candidacy of CACNA2D2 as a disease gene associated with a phenotypic spectrum of neurological disease that include features of developmental and epileptic encephalopathy, ataxia, and cerebellar atrophy. Age at presentation may affect apparent penetrance of neurogenetic trait manifestations and of a particular clinical neurological endophenotype, for example, seizures or ataxia.

Bi-allelic GOT2 Mutations Cause a Treatable Malate-Aspartate Shuttle-Related Encephalopathy. - van Karnebeek, Clara D M; Ramos, Rúben J; Wen, Xiao-Yan; Tarailo-Graovac, Maja; Gleeson, Joseph G; Skrypnyk, Cristina; Brand-Arzamendi, Koroboshka; Karbassi, Farhad; Issa, Mahmoud Y; van der Lee, Robin; Drögemöller, Britt I; Koster, Janet; et al. (Am J Hum Genet, 2019)
Early-infantile encephalopathies with epilepsy are devastating conditions mandating an accurate diagnosis to guide proper management. Whole-exome sequencing was used to investigate the disease etiology in four children from independent families with intellectual disability and epilepsy, revealing bi-allelic GOT2 mutations. In-depth metabolic studies in individual 1 showed low plasma serine, hypercitrullinemia, hyperlactatemia, and hyperammonemia. The epilepsy was serine and pyridoxine responsive. Functional consequences of observed mutations were tested by measuring enzyme activity and by cell and animal models. Zebrafish and mouse models were used to validate brain developmental and functional defects and to test therapeutic strategies. GOT2 encodes the mitochondrial glutamate oxaloacetate transaminase. GOT2 enzyme activity was deficient in fibroblasts with bi-allelic mutations. GOT2, a member of the malate-aspartate shuttle, plays an essential role in the intracellular NAD(H) redox balance. De novo serine biosynthesis was impaired in fibroblasts with GOT2 mutations and GOT2-knockout HEK293 cells. Correcting the highly oxidized cytosolic NAD-redox state by pyruvate supplementation restored serine biosynthesis in GOT2-deficient cells. Knockdown of got2a in zebrafish resulted in a brain developmental defect associated with seizure-like electroencephalography spikes, which could be rescued by supplying pyridoxine in embryo water. Both pyridoxine and serine synergistically rescued embryonic developmental defects in zebrafish got2a morphants. The two treated individuals reacted favorably to their treatment. Our data provide a mechanistic basis for the biochemical abnormalities in GOT2 deficiency that may also hold for other MAS defects.

Bi-allelic Mutations in FAM149B1 Cause Abnormal Primary Cilium and a Range of Ciliopathy Phenotypes in Humans. - Shaheen, Ranad; Jiang, Nan; Alzahrani, Fatema; Ewida, Nour; Al-Sheddi, Tarfa; Alobeid, Eman; Musaev, Damir; Stanley, Valentina; Hashem, Mais; Ibrahim, Niema; Abdulwahab, Firdous; Alshenqiti, Abduljabbar; et al. (Am J Hum Genet, 2019)
Ciliopathies are clinical disorders of the primary cilium with widely recognized phenotypic and genetic heterogeneity. In two Arab consanguineous families, we mapped a ciliopathy phenotype that most closely matches Joubert syndrome (hypotonia, developmental delay, typical facies, oculomotor apraxia, polydactyly, and subtle posterior fossa abnormalities) to a single locus in which a founder homozygous truncating variant in FAM149B1 was identified by exome sequencing. We subsequently identified a third Arab consanguineous multiplex family in which the phenotype of Joubert syndrome/oral-facial-digital syndrome (OFD VI) was found to co-segregate with the same founder variant in FAM149B1. Independently, autozygosity mapping and exome sequencing in a consanguineous Turkish family with Joubert syndrome highlighted a different homozygous truncating variant in the same gene. FAM149B1 encodes a protein of unknown function. Mutant fibroblasts were found to have normal ciliogenesis potential. However, distinct cilia-related abnormalities were observed in these cells: abnormal accumulation IFT complex at the distal tips of the cilia, which assumed bulbous appearance, increased length of the primary cilium, and dysregulated SHH signaling. We conclude that FAM149B1 is required for normal ciliary biology and that its deficiency results in a range of ciliopathy phenotypes in humans along the spectrum of Joubert syndrome.

Biallelic mutations in valyl-tRNA synthetase gene VARS are associated with a progressive neurodevelopmental epileptic encephalopathy. - Friedman, Jennifer; Smith, Desiree E; Issa, Mahmoud Y; Stanley, Valentina; Wang, Rengang; Mendes, Marisa I; Wright, Meredith S; Wigby, Kristen; Hildreth, Amber; Crawford, John R; Koehler, Alanna E; Chowdhury, Shimul; et al. (Nat Commun, 2019)
Aminoacyl-tRNA synthetases (ARSs) function to transfer amino acids to cognate tRNA molecules, which are required for protein translation. To date, biallelic mutations in 31 ARS genes are known to cause recessive, early-onset severe multi-organ diseases. VARS encodes the only known valine cytoplasmic-localized aminoacyl-tRNA synthetase. Here, we report seven patients from five unrelated families with five different biallelic missense variants in VARS. Subjects present with a range of global developmental delay, epileptic encephalopathy and primary or progressive microcephaly. Longitudinal assessment demonstrates progressive cortical atrophy and white matter volume loss. Variants map to the VARS tRNA binding domain and adjacent to the anticodon domain, and disrupt highly conserved residues. Patient primary cells show intact VARS protein but reduced enzymatic activity, suggesting partial loss of function. The implication of VARS in pediatric neurodegeneration broadens the spectrum of human diseases due to mutations in tRNA synthetase genes.
Keywords: Alleles; Anticodon; Child; Child, Preschool; Disease Progression; Epilepsy; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Mutation; Neurodevelopmental Disorders; Pedigree; Protein Biosynthesis; Protein Interaction Domains and Motifs; RNA, Transfer; Valine-tRNA Ligase; Whole Exome Sequencing; Whole Genome Sequencing

Bi-allelic Variants in DYNC1I2 Cause Syndromic Microcephaly with Intellectual Disability, Cerebral Malformations, and Dysmorphic Facial Features. - Ansar, Muhammad; Ullah, Farid; Paracha, Sohail A; Adams, Darius J; Lai, Abbe; Pais, Lynn; Iwaszkiewicz, Justyna; Millan, Francisca; Sarwar, Muhammad T; Agha, Zehra; Shah, Sayyed Fahim; Qaisar, Azhar Ali; et al. (Am J Hum Genet, 2019)
Cargo transport along the cytoplasmic microtubular network is essential for neuronal function, and cytoplasmic dynein-1 is an established molecular motor that is critical for neurogenesis and homeostasis. We performed whole-exome sequencing, homozygosity mapping, and chromosomal microarray studies in five individuals from three independent pedigrees and identified likely-pathogenic variants in DYNC1I2 (Dynein Cytoplasmic 1 Intermediate Chain 2), encoding a component of the cytoplasmic dynein 1 complex. In a consanguineous Pakistani family with three affected individuals presenting with microcephaly, severe intellectual disability, simplification of cerebral gyration, corpus callosum hypoplasia, and dysmorphic facial features, we identified a homozygous splice donor site variant (GenBank: NM_001378.2:c.607+1G>A). We report two additional individuals who have similar neurodevelopmental deficits and craniofacial features and harbor deleterious variants; one individual bears a c.740A>G (p.Tyr247Cys) change in trans with a 374 kb deletion encompassing DYNC1I2, and an unrelated individual harbors the compound-heterozygous variants c.868C>T (p.Gln290) and c.740A>G (p.Tyr247Cys). Zebrafish larvae subjected to CRISPR-Cas9 gene disruption or transient suppression of dync1i2a displayed significantly altered craniofacial patterning with concomitant reduction in head size. We monitored cell death and cell cycle progression in dync1i2a zebrafish models and observed significantly increased apoptosis, likely due to prolonged mitosis caused by abnormal spindle morphology, and this finding offers initial insights into the cellular basis of microcephaly. Additionally, complementation studies in zebrafish demonstrate that p.Tyr247Cys attenuates gene function, consistent with protein structural analysis. Our genetic and functional data indicate that DYNC1I2 dysfunction probably causes an autosomal-recessive microcephaly syndrome and highlight further the critical roles of the dynein-1 complex in neurodevelopment.

Bi-allelic Variants in TONSL Cause SPONASTRIME Dysplasia and a Spectrum of Skeletal Dysplasia Phenotypes. - Burrage, Lindsay C; Reynolds, John J; Baratang, Nissan Vida; Phillips, Jennifer B; Wegner, Jeremy; McFarquhar, Ashley; Higgs, Martin R; Christiansen, Audrey E; Lanza, Denise G; Seavitt, John R; Jain, Mahim; Li, Xiaohui; et al. (Am J Hum Genet, 2019)
SPONASTRIME dysplasia is an autosomal-recessive spondyloepimetaphyseal dysplasia characterized by spine (spondylar) abnormalities, midface hypoplasia with a depressed nasal bridge, metaphyseal striations, and disproportionate short stature. Scoliosis, coxa vara, childhood cataracts, short dental roots, and hypogammaglobulinemia have also been reported in this disorder. Although an autosomal-recessive inheritance pattern has been hypothesized, pathogenic variants in a specific gene have not been discovered in individuals with SPONASTRIME dysplasia. Here, we identified bi-allelic variants in TONSL, which encodes the Tonsoku-like DNA repair protein, in nine subjects (from eight families) with SPONASTRIME dysplasia, and four subjects (from three families) with short stature of varied severity and spondylometaphyseal dysplasia with or without immunologic and hematologic abnormalities, but no definitive metaphyseal striations at diagnosis. The finding of early embryonic lethality in a Tonsl murine model and the discovery of reduced length, spinal abnormalities, reduced numbers of neutrophils, and early lethality in a tonsl zebrafish model both support the hypomorphic nature of the identified TONSL variants. Moreover, functional studies revealed increased amounts of spontaneous replication fork stalling and chromosomal aberrations, as well as fewer camptothecin (CPT)-induced RAD51 foci in subject-derived cell lines. Importantly, these cellular defects were rescued upon re-expression of wild-type (WT) TONSL; this rescue is consistent with the hypothesis that hypomorphic TONSL variants are pathogenic. Overall, our studies in humans, mice, zebrafish, and subject-derived cell lines confirm that pathogenic variants in TONSL impair DNA replication and homologous recombination-dependent repair processes, and they lead to a spectrum of skeletal dysplasia phenotypes with numerous extra-skeletal manifestations.

Biallelic VARS variants cause developmental encephalopathy with microcephaly that is recapitulated in vars knockout zebrafish. - Siekierska, Aleksandra; Stamberger, Hannah; Deconinck, Tine; Oprescu, Stephanie N; Partoens, Michèle; Zhang, Yifan; Sourbron, Jo; Adriaenssens, Elias; Mullen, Patrick; Wiencek, Patrick; Hardies, Katia; Lee, Jeong-Soo; et al. (Nat Commun, 2019)
Aminoacyl tRNA synthetases (ARSs) link specific amino acids with their cognate transfer RNAs in a critical early step of protein translation. Mutations in ARSs have emerged as a cause of recessive, often complex neurological disease traits. Here we report an allelic series consisting of seven novel and two previously reported biallelic variants in valyl-tRNA synthetase (VARS) in ten patients with a developmental encephalopathy with microcephaly, often associated with early-onset epilepsy. In silico, in vitro, and yeast complementation assays demonstrate that the underlying pathomechanism of these mutations is most likely a loss of protein function. Zebrafish modeling accurately recapitulated some of the key neurological disease traits. These results provide both genetic and biological insights into neurodevelopmental disease and pave the way for further in-depth research on ARS related recessive disorders and precision therapies.
Keywords: Alleles; Animals; Brain Diseases; Cell Line; Disease Models, Animal; Epilepsy; Female; Fibroblasts; Gene Knockout Techniques; Genetic Predisposition to Disease; Humans; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Neurodevelopmental Disorders; Pedigree; Prosencephalon; Valine-tRNA Ligase; Zebrafish

Bioinformatics-Based Identification of Expanded Repeats: A Non-reference Intronic Pentamer Expansion in RFC1 Causes CANVAS. - Rafehi, Haloom; Szmulewicz, David J; Bennett, Mark F; Sobreira, Nara L M; Pope, Kate; Smith, Katherine R; Gillies, Greta; Diakumis, Peter; Dolzhenko, Egor; Eberle, Michael A; Barcina, María García; Breen, David P; et al. (Am J Hum Genet, 2019)
Genomic technologies such as next-generation sequencing (NGS) are revolutionizing molecular diagnostics and clinical medicine. However, these approaches have proven inefficient at identifying pathogenic repeat expansions. Here, we apply a collection of bioinformatics tools that can be utilized to identify either known or novel expanded repeat sequences in NGS data. We performed genetic studies of a cohort of 35 individuals from 22 families with a clinical diagnosis of cerebellar ataxia with neuropathy and bilateral vestibular areflexia syndrome (CANVAS). Analysis of whole-genome sequence (WGS) data with five independent algorithms identified a recessively inherited intronic repeat expansion [(AAGGG)] in the gene encoding Replication Factor C1 (RFC1). This motif, not reported in the reference sequence, localized to an Alu element and replaced the reference (AAAAG) short tandem repeat. Genetic analyses confirmed the pathogenic expansion in 18 of 22 CANVAS-affected families and identified a core ancestral haplotype, estimated to have arisen in Europe more than twenty-five thousand years ago. WGS of the four RFC1-negative CANVAS-affected families identified plausible variants in three, with genomic re-diagnosis of SCA3, spastic ataxia of the Charlevoix-Saguenay type, and SCA45. This study identified the genetic basis of CANVAS and demonstrated that these improved bioinformatics tools increase the diagnostic utility of WGS to determine the genetic basis of a heterogeneous group of clinically overlapping neurogenetic disorders.

Cerebral hypomyelination associated with biallelic variants of FIG4. - Lenk, Guy M; Berry, Ian R; Stutterd, Chloe A; Blyth, Moira; Green, Lydia; Vadlamani, Gayatri; Warren, Daniel; Craven, Ian; Fanjul-Fernandez, Miriam; Rodriguez-Casero, Victoria; Lockhart, Paul J; Vanderver, Adeline; et al. (Hum Mutat, 2019)
The lipid phosphatase gene FIG4 is responsible for Yunis-Varón syndrome and Charcot-Marie-Tooth disease Type 4J, a peripheral neuropathy. We now describe four families with FIG4 variants and prominent abnormalities of central nervous system (CNS) white matter (leukoencephalopathy), with onset in early childhood, ranging from severe hypomyelination to mild undermyelination, in addition to peripheral neuropathy. Affected individuals inherited biallelic FIG4 variants from heterozygous parents. Cultured fibroblasts exhibit enlarged vacuoles characteristic of FIG4 dysfunction. Two unrelated families segregate the same G > A variant in the +1 position of intron 21 in the homozygous state in one family and compound heterozygous in the other. This mutation in the splice donor site of exon 21 results in read-through from exon 20 into intron 20 and truncation of the final 115 C-terminal amino acids of FIG4, with retention of partial function. The observed CNS white matter disorder in these families is consistent with the myelination defects in the FIG4 null mouse and the known role of FIG4 in oligodendrocyte maturation. The families described here the expanded clinical spectrum of FIG4 deficiency to include leukoencephalopathy.

Characterization of Rare Variants in MC4R in African American and Latino Children With Severe Early-Onset Obesity. - De Rosa, Maria Caterina; Chesi, Alessandra; McCormack, Shana; Zhou, Justin; Weaver, Benjamin; McDonald, Molly; Christensen, Sinead; Liimatta, Kalle; Rosenbaum, Michael; Hakonarson, Hakon; Doege, Claudia A; Grant, Struan F A; et al. (J Clin Endocrinol Metab, 2019)
CONTEXT: Mutations in melanocortin receptor (MC4R) are the most common cause of monogenic obesity in children of European ancestry, but little is known about their prevalence in children from the minority populations in the United States. OBJECTIVE: This study aims to identify the prevalence of MC4R mutations in children with severe early-onset obesity of African American or Latino ancestry. DESIGN AND SETTING: Participants were recruited from the weight management clinics at two hospitals and from the institutional biobank at a third hospital. Sequencing of the MC4R gene was performed by whole exome or Sanger sequencing. Functional testing was performed to establish the surface expression of the receptor and cAMP response to its cognate ligand α-melanocyte-stimulating hormone. PARTICIPANTS: Three hundred twelve children (1 to 18 years old, 50% girls) with body mass index (BMI) >120% of 95th percentile of Centers for Disease Control and Prevention 2000 growth charts at an age <6 years, with no known pathological cause of obesity, were enrolled. RESULTS: Eight rare MC4R mutations (2.6%) were identified in this study [R7S, F202L (n = 2), M215I, G252D, V253I, I269N, and F284I], three of which were not previously reported (G252D, F284I, and R7S). The pathogenicity of selected variants was confirmed by prior literature reports or functional testing. There was no significant difference in the BMI or height trajectories of children with or without MC4R mutations in this cohort. CONCLUSIONS: Although the prevalence of MC4R mutations in this cohort was similar to that reported for obese children of European ancestry, some of the variants were novel.

Clinical exome sequencing reveals locus heterogeneity and phenotypic variability of cohesinopathies. - Yuan, Bo; Neira, Juanita; Pehlivan, Davut; Santiago-Sim, Teresa; Song, Xiaofei; Rosenfeld, Jill; Posey, Jennifer E; Patel, Vipulkumar; Jin, Weihong; Adam, Margaret P; Baple, Emma L; Dean, John; et al. (Genet Med, 2019)
PURPOSE: Defects in the cohesin pathway are associated with cohesinopathies, notably Cornelia de Lange syndrome (CdLS). We aimed to delineate pathogenic variants in known and candidate cohesinopathy genes from a clinical exome perspective. METHODS: We retrospectively studied patients referred for clinical exome sequencing (CES, N = 10,698). Patients with causative variants in novel or recently described cohesinopathy genes were enrolled for phenotypic characterization. RESULTS: Pathogenic or likely pathogenic single-nucleotide and insertion/deletion variants (SNVs/indels) were identified in established disease genes including NIPBL (N = 5), SMC1A (N = 14), SMC3 (N = 4), RAD21 (N = 2), and HDAC8 (N = 8). The phenotypes in this genetically defined cohort skew towards the mild end of CdLS spectrum as compared with phenotype-driven cohorts. Candidate or recently reported cohesinopathy genes were supported by de novo SNVs/indels in STAG1 (N = 3), STAG2 (N = 5), PDS5A (N = 1), and WAPL (N = 1), and one inherited SNV in PDS5A. We also identified copy-number deletions affecting STAG1 (two de novo, one of unknown inheritance) and STAG2 (one of unknown inheritance). Patients with STAG1 and STAG2 variants presented with overlapping features yet without characteristic facial features of CdLS. CONCLUSION: CES effectively identified disease-causing alleles at the mild end of the cohensinopathy spectrum and enabled characterization of candidate disease genes.
Keywords: Adolescent; Alleles; Antigens, Nuclear; Biological Variation, Population; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Cohort Studies; De Lange Syndrome; Exome; Female; Gene Frequency; Genetic Heterogeneity; Humans; INDEL Mutation; Male; Mutation; Nuclear Proteins; Phenotype; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Retrospective Studies; Whole Exome Sequencing

Clinical, genetic, and pathologic characterization of Mexican founder mutation c.1387A>G. - Lee, Angela J; Jones, Karra A; Butterfield, Russell J; Cox, Mary O; Konersman, Chamindra G; Grosmann, Carla; Abdenur, Jose E; Boyer, Monica; Beson, Brent; Wang, Ching; Dowling, James J; Gibbons, Melissa A; et al. (Neurol Genet, 2019)
Objective: To characterize the clinical phenotype, genetic origin, and muscle pathology of patients with the c.1387A>G mutation. Methods: Standardized clinical data were collected for all patients known to the authors with c.1387A>G mutations in . Muscle biopsies were reviewed and used for histopathology, immunostaining, Western blotting, and DNA extraction. Genetic analysis was performed on extracted DNA. Results: We report the clinical phenotypes of 6 patients homozygous for the c.1387A>G mutation in . Onset of symptoms was <2 years, and 5 of the 6 patients never learned to walk. Brain MRIs were normal. Cognition was normal to mildly impaired. Microarray analysis of 5 homozygous c.1387A>G patients revealed a 500-kb region of shared homozygosity at 19q13.32, including . All 4 muscle biopsies available for review showed end-stage dystrophic pathology, near absence of glycosylated α-dystroglycan (α-DG) by immunofluorescence, and reduced molecular weight of α-DG compared with controls and patients with homozygous c.826C>A limb-girdle muscular dystrophy. Conclusions: The clinical features and muscle pathology in these newly reported patients homozygous for c.1387A>G confirm that this mutation causes congenital muscular dystrophy. The clinical severity might be explained by the greater reduction in α-DG glycosylation compared with that seen with the c.826C>A mutation. The shared region of homozygosity at 19q13.32 indicates that c.1387A>G is a founder mutation with an estimated age of 60 generations (∼1,200-1,500 years).

Clinical Spectrum and Functional Consequences Associated with Bi-Allelic Pathogenic Variants. - Rius, Rocio; Van Bergen, Nicole J; Compton, Alison G; Riley, Lisa G; Kava, Maina P; Balasubramaniam, Shanti; Amor, David J; Fanjul-Fernandez, Miriam; Cowley, Mark J; Fahey, Michael C; Koenig, Mary K; Enns, Gregory M; et al. (J Clin Med, 2019)
(PNPase-polynucleotide phosphorylase) is involved in multiple RNA processing functions in the mitochondria. Bi-allelic pathogenic variants cause heterogeneous clinical phenotypes affecting multiple organs without any established genotype-phenotype correlations. Defects in PNPase can cause variable combined respiratory chain complex defects. Recently, it has been suggested that PNPase can lead to activation of an innate immune response. To better understand the clinical and molecular spectrum of patients with bi-allelic variants, we captured detailed clinical and molecular phenotypes of all 17 patients reported in the literature, plus seven new patients, including a 78-year-old male with the longest reported survival. A functional follow-up of genomic sequencing by cDNA studies confirmed a splicing defect in a novel, apparently synonymous, variant. Patient fibroblasts showed an accumulation of mitochondrial unprocessed transcripts, while blood showed an increased interferon response. Our findings suggest that functional analyses of the RNA processing function of PNPase are more sensitive than testing downstream defects in oxidative phosphorylation (OXPHPOS) enzyme activities. This research extends our knowledge of the clinical and functional consequences of bi-allelic pathogenic variants that may guide management and further efforts into understanding the pathophysiological mechanisms for therapeutic development.

COL4A1 mutations as a potential novel cause of autosomal dominant CAKUT in humans. - Kitzler, Thomas M; Schneider, Ronen; Kohl, Stefan; Kolvenbach, Caroline M; Connaughton, Dervla M; Dai, Rufeng; Mann, Nina; Nakayama, Makiko; Majmundar, Amar J; Wu, Chen-Han W; Kari, Jameela A; El Desoky, Sherif M; et al. (Hum Genet, 2019)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of chronic kidney disease (~ 45%) that manifests before 30 years of age. The genetic locus containing COL4A1 (13q33-34) has been implicated in vesicoureteral reflux (VUR), but mutations in COL4A1 have not been reported in CAKUT. We hypothesized that COL4A1 mutations cause CAKUT in humans. We performed whole exome sequencing (WES) in 550 families with CAKUT. As negative control cohorts we used WES sequencing data from patients with nephronophthisis (NPHP) with no genetic cause identified (n = 257) and with nephrotic syndrome (NS) due to monogenic causes (n = 100). We identified a not previously reported heterozygous missense variant in COL4A1 in three siblings with isolated VUR. When examining 549 families with CAKUT, we identified nine additional different heterozygous missense mutations in COL4A1 in 11 individuals from 11 unrelated families with CAKUT, while no COL4A1 mutations were identified in a control cohort with NPHP and only one in the cohort with NS. Most individuals (12/14) had isolated CAKUT with no extrarenal features. The predominant phenotype was VUR (9/14). There were no clinical features of the COL4A1-related disorders (e.g., HANAC syndrome, porencephaly, tortuosity of retinal arteries). Whereas COL4A1-related disorders are typically caused by glycine substitutions in the collagenous domain (84.4% of variants), only one variant in our cohort is a glycine substitution within the collagenous domain (1/10). We identified heterozygous COL4A1 mutations as a potential novel autosomal dominant cause of CAKUT that is allelic to the established COL4A1-related disorders and predominantly caused by non-glycine substitutions.
Keywords: Alleles; Amino Acid Substitution; Collagen Type IV; Computational Biology; Congenital Abnormalities; Databases, Genetic; DNA Mutational Analysis; Evolution, Molecular; Female; Genetic Association Studies; Genetic Loci; Genomics; Heterozygote; Humans; Kidney; Kidney Diseases, Cystic; Male; Mutation; Nephrotic Syndrome; Phenotype; Urinary Tract; Web Browser; Whole Exome Sequencing

A combined immunodeficiency with severe infections, inflammation, and allergy caused by ARPC1B deficiency. - Volpi, Stefano; Cicalese, Maria Pia; Tuijnenburg, Paul; Tool, Anton T J; Cuadrado, Eloy; Abu-Halaweh, Marwan; Ahanchian, Hamid; Alzyoud, Raed; Akdemir, Zeynep Coban; Barzaghi, Federica; Blank, Alexander; Boisson, Bertrand; et al. (J Allergy Clin Immunol, 2019)

Complex Compound Inheritance of Lethal Lung Developmental Disorders Due to Disruption of the TBX-FGF Pathway. - Karolak, Justyna A; Vincent, Marie; Deutsch, Gail; Gambin, Tomasz; Cogné, Benjamin; Pichon, Olivier; Vetrini, Francesco; Mefford, Heather C; Dines, Jennifer N; Golden-Grant, Katie; Dipple, Katrina; Freed, Amanda S; et al. (Am J Hum Genet, 2019)
Primary defects in lung branching morphogenesis, resulting in neonatal lethal pulmonary hypoplasias, are incompletely understood. To elucidate the pathogenetics of human lung development, we studied a unique collection of samples obtained from deceased individuals with clinically and histopathologically diagnosed interstitial neonatal lung disorders: acinar dysplasia (n = 14), congenital alveolar dysplasia (n = 2), and other lethal lung hypoplasias (n = 10). We identified rare heterozygous copy-number variant deletions or single-nucleotide variants (SNVs) involving TBX4 (n = 8 and n = 2, respectively) or FGF10 (n = 2 and n = 2, respectively) in 16/26 (61%) individuals. In addition to TBX4, the overlapping ∼2 Mb recurrent and nonrecurrent deletions at 17q23.1q23.2 identified in seven individuals with lung hypoplasia also remove a lung-specific enhancer region. Individuals with coding variants involving either TBX4 or FGF10 also harbored at least one non-coding SNV in the predicted lung-specific enhancer region, which was absent in 13 control individuals with the overlapping deletions but without any structural lung anomalies. The occurrence of rare coding variants involving TBX4 or FGF10 with the putative hypomorphic non-coding SNVs implies a complex compound inheritance of these pulmonary hypoplasias. Moreover, they support the importance of TBX4-FGF10-FGFR2 epithelial-mesenchymal signaling in human lung organogenesis and help to explain the histopathological continuum observed in these rare lethal developmental disorders of the lung.
Keywords: DNA Copy Number Variations; Female; Fibroblast Growth Factor 10; Gene Expression Regulation; Gestational Age; Humans; Infant, Newborn; Infant, Newborn, Diseases; Lung; Lung Diseases; Male; Maternal Inheritance; Organogenesis; Paternal Inheritance; Pedigree; Polymorphism, Single Nucleotide; Receptor, Fibroblast Growth Factor, Type 2; Signal Transduction; T-Box Domain Proteins

Contribution of noncoding pathogenic variants to RPGRIP1-mediated inherited retinal degeneration. - Jamshidi, Farzad; Place, Emily M; Mehrotra, Sudeep; Navarro-Gomez, Daniel; Maher, Mathew; Branham, Kari E; Valkanas, Elise; Cherry, Timothy J; Lek, Monkol; Macarthur, Daniel; Pierce, Eric A; Bujakowska, Kinga M (Genet Med, 2019)
PURPOSE: With the advent of gene therapies for inherited retinal degenerations (IRDs), genetic diagnostics will have an increasing role in clinical decision-making. Yet the genetic cause of disease cannot be identified using exon-based sequencing for a significant portion of patients. We hypothesized that noncoding pathogenic variants contribute significantly to the genetic causality of IRDs and evaluated patients with single coding pathogenic variants in RPGRIP1 to test this hypothesis. METHODS: IRD families underwent targeted panel sequencing. Unsolved cases were explored by exome and genome sequencing looking for additional pathogenic variants. Candidate pathogenic variants were then validated by Sanger sequencing, quantitative polymerase chain reaction, and in vitro splicing assays in two cell lines analyzed through amplicon sequencing. RESULTS: Among 1722 families, 3 had biallelic loss-of-function pathogenic variants in RPGRIP1 while 7 had a single disruptive coding pathogenic variants. Exome and genome sequencing revealed potential noncoding pathogenic variants in these 7 families. In 6, the noncoding pathogenic variants were shown to lead to loss of function in vitro. CONCLUSION: Noncoding pathogenic variants were identified in 6 of 7 families with single coding pathogenic variants in RPGRIP1. The results suggest that noncoding pathogenic variants contribute significantly to the genetic causality of IRDs and RPGRIP1-mediated IRDs are more common than previously thought.
Keywords: Adult; Chromosome Mapping; DNA Mutational Analysis; DNA, Intergenic; Female; HEK293 Cells; Humans; Male; Mutation; Pedigree; Proteins; Retinal Degeneration; Whole Exome Sequencing; Whole Genome Sequencing

Copy number variant and runs of homozygosity detection by microarrays enabled more precise molecular diagnoses in 11,020 clinical exome cases. - Dharmadhikari, Avinash V; Ghosh, Rajarshi; Yuan, Bo; Liu, Pengfei; Dai, Hongzheng; Al Masri, Sami; Scull, Jennifer; Posey, Jennifer E; Jiang, Allen H; He, Weimin; Vetrini, Francesco; Braxton, Alicia A; et al. (Genome Med, 2019)
BACKGROUND: Exome sequencing (ES) has been successfully applied in clinical detection of single nucleotide variants (SNVs) and small indels. However, identification of copy number variants (CNVs) using ES data remains challenging. The purpose of this study is to understand the contribution of CNVs and copy neutral runs of homozygosity (ROH) in molecular diagnosis of patients referred for ES. METHODS: In a cohort of 11,020 consecutive ES patients, an Illumina SNP array analysis interrogating mostly coding SNPs was performed as a quality control (QC) measurement and for CNV/ROH detection. Among these patients, clinical chromosomal microarray analysis (CMA) was performed at Baylor Genetics (BG) on 3229 patients, either before, concurrently, or after ES. We retrospectively analyzed the findings from CMA and the QC array. RESULTS: The QC array can detect ~ 70% of pathogenic/likely pathogenic CNVs (PCNVs) detectable by CMA. Out of the 11,020 ES cases, the QC array identified PCNVs in 327 patients and uniparental disomy (UPD) disorder-related ROH in 10 patients. The overall PCNV/UPD detection rate was 5.9% in the 3229 ES patients who also had CMA at BG; PCNV/UPD detection rate was higher in concurrent ES and CMA than in ES with prior CMA (7.2% vs 4.6%). The PCNVs/UPD contributed to the molecular diagnoses in 17.4% (189/1089) of molecularly diagnosed ES cases with CMA and were estimated to contribute in 10.6% of all molecularly diagnosed ES cases. Dual diagnoses with both PCNVs and SNVs were detected in 38 patients. PCNVs affecting single recessive disorder genes in a compound heterozygous state with SNVs were detected in 4 patients, and homozygous deletions (mostly exonic deletions) were detected in 17 patients. A higher PCNV detection rate was observed for patients with syndromic phenotypes and/or cardiovascular abnormalities. CONCLUSIONS: Our clinical genomics study demonstrates that detection of PCNV/UPD through the QC array or CMA increases ES diagnostic rate, provides more precise molecular diagnosis for dominant as well as recessive traits, and enables more complete genetic diagnoses in patients with dual or multiple molecular diagnoses. Concurrent ES and CMA using an array with exonic coverage for disease genes enables most effective detection of both CNVs and SNVs and therefore is recommended especially in time-sensitive clinical situations.

CTCF variants in 39 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum. - Konrad, Enrico D H; Nardini, Niels; Caliebe, Almuth; Nagel, Inga; Young, Dana; Horvath, Gabriella; Santoro, Stephanie L; Shuss, Christine; Ziegler, Alban; Bonneau, Dominique; Kempers, Marlies; Pfundt, Rolph; et al. (Genet Med, 2019)
PURPOSE: Pathogenic variants in the chromatin organizer CTCF were previously reported in seven individuals with a neurodevelopmental disorder (NDD). METHODS: Through international collaboration we collected data from 39 subjects with variants in CTCF. We performed transcriptome analysis on RNA from blood samples and utilized Drosophila melanogaster to investigate the impact of Ctcf dosage alteration on nervous system development and function. RESULTS: The individuals in our cohort carried 2 deletions, 8 likely gene-disruptive, 2 splice-site, and 20 different missense variants, most of them de novo. Two cases were familial. The associated phenotype was of variable severity extending from mild developmental delay or normal IQ to severe intellectual disability. Feeding difficulties and behavioral abnormalities were common, and variable other findings including growth restriction and cardiac defects were observed. RNA-sequencing in five individuals identified 3828 deregulated genes enriched for known NDD genes and biological processes such as transcriptional regulation. Ctcf dosage alteration in Drosophila resulted in impaired gross neurological functioning and learning and memory deficits. CONCLUSION: We significantly broaden the mutational and clinical spectrum ofCTCF-associated NDDs. Our data shed light onto the functional role of CTCF by identifying deregulated genes and show that Ctcf alterations result in nervous system defects in Drosophila.

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

De Novo Pathogenic Variants in N-cadherin Cause a Syndromic Neurodevelopmental Disorder with Corpus Collosum, Axon, Cardiac, Ocular, and Genital Defects. - Accogli, Andrea; Calabretta, Sara; St-Onge, Judith; Boudrahem-Addour, Nassima; Dionne-Laporte, Alexandre; Joset, Pascal; Azzarello-Burri, Silvia; Rauch, Anita; Krier, Joel; Fieg, Elizabeth; Pallais, Juan C; McConkie-Rosell, Allyn; et al. (Am J Hum Genet, 2019)
Cadherins constitute a family of transmembrane proteins that mediate calcium-dependent cell-cell adhesion. The extracellular domain of cadherins consists of extracellular cadherin (EC) domains, separated by calcium binding sites. The EC interacts with other cadherin molecules in cis and in trans to mechanically hold apposing cell surfaces together. CDH2 encodes N-cadherin, whose essential roles in neural development include neuronal migration and axon pathfinding. However, CDH2 has not yet been linked to a Mendelian neurodevelopmental disorder. Here, we report de novo heterozygous pathogenic variants (seven missense, two frameshift) in CDH2 in nine individuals with a syndromic neurodevelopmental disorder characterized by global developmental delay and/or intellectual disability, variable axon pathfinding defects (corpus callosum agenesis or hypoplasia, mirror movements, Duane anomaly), and ocular, cardiac, and genital anomalies. All seven missense variants (c.1057G>A [p.Asp353Asn]; c.1789G>A [p.Asp597Asn]; c.1789G>T [p.Asp597Tyr]; c.1802A>C [p.Asn601Thr]; c.1839C>G [p.Cys613Trp]; c.1880A>G [p.Asp627Gly]; c.2027A>G [p.Tyr676Cys]) result in substitution of highly conserved residues, and six of seven cluster within EC domains 4 and 5. Four of the substitutions affect the calcium-binding site in the EC4-EC5 interdomain. We show that cells expressing these variants in the EC4-EC5 domains have a defect in cell-cell adhesion; this defect includes impaired binding in trans with N-cadherin-WT expressed on apposing cells. The two frameshift variants (c.2563_2564delCT [p.Leu855Valfs4]; c.2564_2567dupTGTT [p.Leu856Phefs5]) are predicted to lead to a truncated cytoplasmic domain. Our study demonstrates that de novo heterozygous variants in CDH2 impair the adhesive activity of N-cadherin, resulting in a multisystemic developmental disorder, that could be named ACOG syndrome (agenesis of corpus callosum, axon pathfinding, cardiac, ocular, and genital defects).

De Novo SOX4 Variants Cause a Neurodevelopmental Disease Associated with Mild Dysmorphism. - Zawerton, Ash; Yao, Baojin; Yeager, J Paige; Pippucci, Tommaso; Haseeb, Abdul; Smith, Joshua D; Wischmann, Lisa; Kühl, Susanne J; Dean, John C S; Pilz, Daniela T; Holder, Susan E; McNeill, Alisdair; et al. (Am J Hum Genet, 2019)
SOX4, together with SOX11 and SOX12, forms group C of SRY-related (SOX) transcription factors. They play key roles, often in redundancy, in multiple developmental pathways, including neurogenesis and skeletogenesis. De novo SOX11 heterozygous mutations have been shown to cause intellectual disability, growth deficiency, and dysmorphic features compatible with mild Coffin-Siris syndrome. Using trio-based exome sequencing, we here identify de novo SOX4 heterozygous missense variants in four children who share developmental delay, intellectual disability, and mild facial and digital morphological abnormalities. SOX4 is highly expressed in areas of active neurogenesis in human fetuses, and sox4 knockdown in Xenopus embryos diminishes brain and whole-body size. The SOX4 variants cluster in the highly conserved, SOX family-specific HMG domain, but each alters a different residue. In silico tools predict that each variant affects a distinct structural feature of this DNA-binding domain, and functional assays demonstrate that these SOX4 proteins carrying these variants are unable to bind DNA in vitro and transactivate SOX reporter genes in cultured cells. These variants are not found in the gnomAD database of individuals with presumably normal development, but 12 other SOX4 HMG-domain missense variants are recorded and all demonstrate partial to full activity in the reporter assay. Taken together, these findings point to specific SOX4 HMG-domain missense variants as the cause of a characteristic human neurodevelopmental disorder associated with mild facial and digital dysmorphism.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Child; Child, Preschool; Coffin-Lowry Syndrome; Cohort Studies; Conserved Sequence; DNA; Female; Heterozygote; HMG-Box Domains; Humans; Male; Mutation, Missense; Neurodevelopmental Disorders; SOXC Transcription Factors; Transcriptional Activation; Xenopus

De Novo Variants Disturbing the Transactivation Capacity of POU3F3 Cause a Characteristic Neurodevelopmental Disorder. - Snijders Blok, Lot; Kleefstra, Tjitske; Venselaar, Hanka; Maas, Saskia; Kroes, Hester Y; Lachmeijer, Augusta M A; van Gassen, Koen L I; Firth, Helen V; Tomkins, Susan; Bodek, Simon; Õunap, Katrin; Wojcik, Monica H; et al. (Am J Hum Genet, 2019)
POU3F3, also referred to as Brain-1, is a well-known transcription factor involved in the development of the central nervous system, but it has not previously been associated with a neurodevelopmental disorder. Here, we report the identification of 19 individuals with heterozygous POU3F3 disruptions, most of which are de novo variants. All individuals had developmental delays and/or intellectual disability and impairments in speech and language skills. Thirteen individuals had characteristic low-set, prominent, and/or cupped ears. Brain abnormalities were observed in seven of eleven MRI reports. POU3F3 is an intronless gene, insensitive to nonsense-mediated decay, and 13 individuals carried protein-truncating variants. All truncating variants that we tested in cellular models led to aberrant subcellular localization of the encoded protein. Luciferase assays demonstrated negative effects of these alleles on transcriptional activation of a reporter with a FOXP2-derived binding motif. In addition to the loss-of-function variants, five individuals had missense variants that clustered at specific positions within the functional domains, and one small in-frame deletion was identified. Two missense variants showed reduced transactivation capacity in our assays, whereas one variant displayed gain-of-function effects, suggesting a distinct pathophysiological mechanism. In bioluminescence resonance energy transfer (BRET) interaction assays, all the truncated POU3F3 versions that we tested had significantly impaired dimerization capacities, whereas all missense variants showed unaffected dimerization with wild-type POU3F3. Taken together, our identification and functional cell-based analyses of pathogenic variants in POU3F3, coupled with a clinical characterization, implicate disruptions of this gene in a characteristic neurodevelopmental disorder.

De novo variants in HK1 associated with neurodevelopmental abnormalities and visual impairment. - Okur, Volkan; Cho, Megan T; van Wijk, Richard; van Oirschot, Brigitte; Picker, Jonathan; Coury, Stephanie A; Grange, Dorothy; Manwaring, Linda; Krantz, Ian; Muraresku, Colleen Clark; Hulick, Peter J; May, Holley; et al. (Eur J Hum Genet, 2019)
Hexokinase 1 (HK1) phosphorylates glucose to glucose-6-phosphate, the first rate-limiting step in glycolysis. Homozygous and heterozygous variants in HK1 have been shown to cause autosomal recessive non-spherocytic hemolytic anemia, autosomal recessive Russe type hereditary motor and sensory neuropathy, and autosomal dominant retinitis pigmentosa (adRP). We report seven patients from six unrelated families with a neurodevelopmental disorder associated with developmental delay, intellectual disability, structural brain abnormality, and visual impairments in whom we identified four novel, de novo missense variants in the N-terminal half of HK1. Hexokinase activity in red blood cells of two patients was normal, suggesting that the disease mechanism is not due to loss of hexokinase enzymatic activity.

Deleterious de novo variants of X-linked ZC4H2 in females cause a variable phenotype with neurogenic arthrogryposis multiplex congenita. - Frints, Suzanna G M; Hennig, Friederike; Colombo, Roberto; Jacquemont, Sebastien; Terhal, Paulien; Zimmerman, Holly H; Hunt, David; Mendelsohn, Bryce A; Kordaß, Ulrike; Webster, Richard; Sinnema, Margje; Abdul-Rahman, Omar; et al. (Hum Mutat, 2019)
Pathogenic variants in the X-linked gene ZC4H2, which encodes a zinc-finger protein, cause an infrequently described syndromic form of arthrogryposis multiplex congenita (AMC) with central and peripheral nervous system involvement. We present genetic and detailed phenotypic information on 23 newly identified families and simplex cases that include 19 affected females from 18 families and 14 affected males from nine families. Of note, the 15 females with deleterious de novo ZC4H2 variants presented with phenotypes ranging from mild to severe, and their clinical features overlapped with those seen in affected males. By contrast, of the nine carrier females with inherited ZC4H2 missense variants that were deleterious in affected male relatives, four were symptomatic. We also compared clinical phenotypes with previously published cases of both sexes and provide an overview on 48 males and 57 females from 42 families. The spectrum of ZC4H2 defects comprises novel and recurrent mostly inherited missense variants in affected males, and de novo splicing, frameshift, nonsense, and partial ZC4H2 deletions in affected females. Pathogenicity of two newly identified missense variants was further supported by studies in zebrafish. We propose ZC4H2 as a good candidate for early genetic testing of males and females with a clinical suspicion of fetal hypo-/akinesia and/or (neurogenic) AMC.

Detailed genetic characteristics of an international large cohort of patients with Stargardt disease: ProgStar study report 8. - Fujinami, Kaoru; Strauss, Rupert W; Chiang, John Pei-Wen; Audo, Isabelle S; Bernstein, Paul S; Birch, David G; Bomotti, Samantha M; Cideciyan, Artur V; Ervin, Ann-Margret; Marino, Meghan J; Sahel, José-Alain; Mohand-Said, Saddek; et al. (Br J Ophthalmol, 2019)
BACKGROUND/AIMS: To describe the genetic characteristics of the cohort enrolled in the international multicentre progression of Stargardt disease 1 (STGD1) studies (ProgStar) and to determine geographic differences based on the allele frequency. METHODS: 345 participants with a clinical diagnosis of STGD1 and harbouring at least one disease-causing ABCA4 variant were enrolled from 9 centres in the USA and Europe. All variants were reviewed and analysis was performed including allele frequency in public databases and pathogenicity predictions. Participants with multiple likely pathogenic variants were classified into four national subgroups (USA, UK, France, Germany), with subsequent comparison analysis of the allele frequency for each prevalent allele. RESULTS: 211 likely pathogenic variants were identified in the total cohort, including missense (63%), splice site alteration (18%), stop (9%) and others. 50 variants were novel. Exclusively missense variants were detected in 139 (50%) of 279 patients with multiple pathogenic variants. The three most prevalent variants of these patients with multiple pathogenic variants were p.G1961E (15%), p.G863A (7%) and c.5461-10 T>C (5%). Subgroup analysis revealed a statistically significant difference between the four recruiting nations in the allele frequency of nine variants. CONCLUSIONS: There is a large spectrum of ABCA4 sequence variants, including 50 novel variants, in a well-characterised cohort thereby further adding to the unique allelic heterogeneity in STGD1. Approximately half of the cohort harbours missense variants only, indicating a relatively mild phenotype of the ProgStar cohort. There are significant differences in allele frequencies between nations, although the three most prevalent variants are shared as frequent variants.
Keywords: Adolescent; Adult; Age of Onset; Aged; ATP-Binding Cassette Transporters; Child; Child, Preschool; Cohort Studies; Databases, Factual; DNA Mutational Analysis; Female; Gene Frequency; Genotyping Techniques; Geography; Humans; Internationality; Macular Degeneration; Male; Middle Aged; Mutation; Polymerase Chain Reaction

Disparities in discovery of pathogenic variants for autosomal recessive non-syndromic hearing impairment by ancestry. - Chakchouk, Imen; Zhang, Di; Zhang, Zhihui; Francioli, Laurent C; Santos-Cortez, Regie Lyn P; Schrauwen, Isabelle; Leal, Suzanne M (Eur J Hum Genet, 2019)
Hearing impairment (HI) is characterized by extensive genetic heterogeneity. To determine the population-specific contribution of known autosomal recessive nonsyndromic (ARNS)HI genes and variants to HI etiology; pathogenic and likely pathogenic (PLP) ARNSHI variants were selected from ClinVar and the Deafness Variation Database and their frequencies were obtained from gnomAD for seven populations. ARNSHI prevalence due to PLP variants varies greatly by population ranging from 96.9 affected per 100,000 individuals for Ashkenazi Jews to 5.2 affected per 100,000 individuals for Africans/African Americans. For Europeans, Finns have the lowest prevalence due to ARNSHI PLP variants with 9.5 affected per 100,000 individuals. For East Asians, Latinos, non-Finish Europeans, and South Asians, ARNSHI prevalence due to PLP variants ranges from 17.1 to 33.7 affected per 100,000 individuals. ARNSHI variants that were previously reported in a single ancestry or family were observed in additional populations, e.g., USH1C p.(Q723*) reported in a Chinese family was the most prevalent pathogenic variant observed in gnomAD for African/African Americans. Variability between populations is due to how extensively ARNSHI has been studied, ARNSHI prevalence and ancestry specific ARNSHI variant architecture which is impacted by population history. Our study demonstrates that additional gene and variant discovery studies are necessary for all populations and particularly for individuals of African ancestry.

Disruptive mutations in TANC2 define a neurodevelopmental syndrome associated with psychiatric disorders. - Guo, Hui; Bettella, Elisa; Marcogliese, Paul C; Zhao, Rongjuan; Andrews, Jonathan C; Nowakowski, Tomasz J; Gillentine, Madelyn A; Hoekzema, Kendra; Wang, Tianyun; Wu, Huidan; Jangam, Sharayu; Liu, Cenying; et al. (Nat Commun, 2019)
Postsynaptic density (PSD) proteins have been implicated in the pathophysiology of neurodevelopmental and psychiatric disorders. Here, we present detailed clinical and genetic data for 20 patients with likely gene-disrupting mutations in TANC2-whose protein product interacts with multiple PSD proteins. Pediatric patients with disruptive mutations present with autism, intellectual disability, and delayed language and motor development. In addition to a variable degree of epilepsy and facial dysmorphism, we observe a pattern of more complex psychiatric dysfunction or behavioral problems in adult probands or carrier parents. Although this observation requires replication to establish statistical significance, it also suggests that mutations in this gene are associated with a variety of neuropsychiatric disorders consistent with its postsynaptic function. We find that TANC2 is expressed broadly in the human developing brain, especially in excitatory neurons and glial cells, but shows a more restricted pattern in Drosophila glial cells where its disruption affects behavioral outcomes.

Distinct patterns of complex rearrangements and a mutational signature of microhomeology are frequently observed in PLP1 copy number gain structural variants. - Bahrambeigi, Vahid; Song, Xiaofei; Sperle, Karen; Beck, Christine R; Hijazi, Hadia; Grochowski, Christopher M; Gu, Shen; Seeman, Pavel; Woodward, Karen J; Carvalho, Claudia M B; Hobson, Grace M; Lupski, James R (Genome Med, 2019)
BACKGROUND: We investigated the features of the genomic rearrangements in a cohort of 50 male individuals with proteolipid protein 1 (PLP1) copy number gain events who were ascertained with Pelizaeus-Merzbacher disease (PMD; MIM: 312080). We then compared our new data to previous structural variant mutagenesis studies involving the Xq22 region of the human genome. The aggregate data from 159 sequenced join-points (discontinuous sequences in the reference genome that are joined during the rearrangement process) were studied. Analysis of these data from 150 individuals enabled the spectrum and relative distribution of the underlying genomic mutational signatures to be delineated. METHODS: Genomic rearrangements in PMD individuals with PLP1 copy number gain events were investigated by high-density customized array or clinical chromosomal microarray analysis and breakpoint junction sequence analysis. RESULTS: High-density customized array showed that the majority of cases (33/50; ~ 66%) present with single duplications, although complex genomic rearrangements (CGRs) are also frequent (17/50; ~ 34%). Breakpoint mapping to nucleotide resolution revealed further previously unknown structural and sequence complexities, even in single duplications. Meta-analysis of all studied rearrangements that occur at the PLP1 locus showed that single duplications were found in ~ 54% of individuals and that, among all CGR cases, triplication flanked by duplications is the most frequent CGR array CGH pattern observed. Importantly, in ~ 32% of join-points, there is evidence for a mutational signature of microhomeology (highly similar yet imperfect sequence matches). CONCLUSIONS: These data reveal a high frequency of CGRs at the PLP1 locus and support the assertion that replication-based mechanisms are prominent contributors to the formation of CGRs at Xq22. We propose that microhomeology can facilitate template switching, by stabilizing strand annealing of the primer using W-C base complementarity, and is a mutational signature for replicative repair.

Dominant PAX2 mutations may cause steroid-resistant nephrotic syndrome and FSGS in children. - Vivante, Asaf; Chacham, Orna Staretz; Shril, Shirlee; Schreiber, Ruth; Mane, Shrikant M; Pode-Shakked, Ben; Soliman, Neveen A; Koneth, Irene; Schiffer, Mario; Anikster, Yair; Hildebrandt, Friedhelm (Pediatr Nephrol, 2019)
BACKGROUND: Heterozygous PAX2 mutations cause renal coloboma syndrome (RCS) [OMIM no. 120330]. RCS is a renal syndromic disease encompassing retinal coloboma and sensorineural hearing loss. Recently, a causative role for PAX2 was reported in adult-onset nephrotic syndrome secondary to focal segmental glomerulosclerosis (FSGS). However, the prevalence of PAX2 mutations among large cohort of children with steroid-resistant nephrotic syndrome (SRNS) and FSGS has not been systematically studied. METHODS: We employed whole-exome sequencing (WES) to identify the percentage of SRNS cases explained by monogenic mutations in known genes of SRNS/FSGS. As PAX2 mutations are not an established cause of childhood FSGS, we evaluated a cohort of 215 unrelated families with SRNS, in whom no underlying genetic etiology had been previously established. RESULTS: Using WES, we identified 3 novel causative heterozygous PAX2 mutations in 3 out of the 215 unrelated index cases studied (1.3%). All three cases were detected in individuals from families with more than one affected and compatible with an autosomal dominant mode of inheritance (3/57 familial cases studied (5.2%)). The clinical diagnosis in three out of four pediatric index patients was done during routine medical evaluation. CONCLUSIONS: Our findings demonstrate high frequency of PAX2 mutations in familial form of SRNS (5.2%) and further expand the phenotypic spectrum of PAX2 heterozygous mutations to include autosomal dominant childhood-onset FSGS. These results highlight the importance of including PAX2 in the list of genes known to cause FSGS in children.

Dominant-negative SOX9 mutations in campomelic dysplasia. - Csukasi, Fabiana; Duran, Ivan; Zhang, Wenjuan; Martin, Jorge H; Barad, Maya; Bamshad, Michael; Weis, Mary Ann; Eyre, David; Krakow, Deborah; Cohn, Daniel H (Hum Mutat, 2019)
Campomelic dysplasia (CD) is an autosomal dominant, perinatal lethal skeletal dysplasia characterized by a small chest and short long bones with bowing of the lower extremities. CD is the result of heterozygosity for mutations in the gene encoding the chondrogenesis master regulator, SOX9. Loss-of-function mutations have been identified in most CD cases so it has been assumed that the disease results from haploinsufficiency for SOX9. Here, we identified distal truncating SOX9 mutations in four unrelated CD cases. The mutations all leave the dimerization and DNA-binding domains intact and cultured chondrocytes from three of the four cases synthesized truncated SOX9. Relative to CD resulting from haploinsufficiency, there was decreased transactivation activity toward a major transcriptional target, COL2A1, consistent with the mutations exerting a dominant-negative effect. For one of the cases, the phenotypic consequence was a very severe form of CD, with a pronounced effect on vertebral and limb development. The data identify a novel molecular mechanism of disease in CD in which the truncated protein leads to a distinct and more significant effect on SOX9 function.

DPAGT1 Deficiency with Encephalopathy (DPAGT1-CDG): Clinical and Genetic Description of 11 New Patients. - Ng, Bobby G; Underhill, Hunter R; Palm, Lars; Bengtson, Per; Rozet, Jean-Michel; Gerber, Sylvie; Munnich, Arnold; Zanlonghi, Xavier; Stevens, Cathy A; Kircher, Martin; Nickerson, Deborah A; Buckingham, Kati J; et al. (JIMD Rep, 2019)
Pathogenic mutations in DPAGT1 cause a rare type of a congenital disorder of glycosylation termed DPAGT1-CDG or, alternatively, a milder version with only myasthenia known as DPAGT1-CMS. Fourteen disease-causing mutations in 28 patients from 10 families have previously been reported to cause the systemic form, DPAGT1-CDG. We here report on another 11 patients from 8 families and add 10 new mutations. Most patients have a very severe disease course, where common findings are pronounced muscular hypotonia, intractable epilepsy, global developmental delay/intellectual disability, and early death. We also present data on three affected females that are young adults and have a somewhat milder, stable disease. Our findings expand both the molecular and clinical knowledge of previously published data but also widen the phenotypic spectrum of DPAGT1-CDG.

Enabling Global Clinical Collaborations on Identifiable Patient Data: The Minerva Initiative. - Nellaker, Christoffer; Alkuraya, Fowzan S; Baynam, Gareth; Bernier, Raphael A; Bernier, Francois P J; Boulanger, Vanessa; Brudno, Michael; Brunner, Han G; Clayton-Smith, Jill; Cogné, Benjamin; Dawkins, Hugh J S; deVries, Bert B A; et al. (Front Genet, 2019)
The clinical utility of computational phenotyping for both genetic and rare diseases is increasingly appreciated; however, its true potential is yet to be fully realized. Alongside the growing clinical and research availability of sequencing technologies, precise deep and scalable phenotyping is required to serve unmet need in genetic and rare diseases. To improve the lives of individuals affected with rare diseases through deep phenotyping, global big data interrogation is necessary to aid our understanding of disease biology, assist diagnosis, and develop targeted treatment strategies. This includes the application of cutting-edge machine learning methods to image data. As with most digital tools employed in health care, there are ethical and data governance challenges associated with using identifiable personal image data. There are also risks with failing to deliver on the patient benefits of these new technologies, the biggest of which is posed by data siloing. The Minerva Initiative has been designed to enable the public good of deep phenotyping while mitigating these ethical risks. Its open structure, enabling collaboration and data sharing between individuals, clinicians, researchers and private enterprise, is key for delivering precision public health.

EphrinB2-EphB4-RASA1 Signaling in Human Cerebrovascular Development and Disease. - Zeng, Xue; Hunt, Ava; Jin, Sheng Chih; Duran, Daniel; Gaillard, Jonathan; Kahle, Kristopher T (Trends Mol Med, 2019)
Recent whole exome sequencing studies in humans have provided novel insight into the importance of the ephrinB2-EphB4-RASA1 signaling axis in cerebrovascular development, corroborating and extending previous work in model systems. Here, we aim to review the human cerebrovascular phenotypes associated with ephrinB2-EphB4-RASA1 mutations, including those recently discovered in Vein of Galen malformation: the most common and severe brain arteriovenous malformation in neonates. We will also discuss emerging paradigms of the molecular and cellular pathophysiology of disease-causing ephrinB2-EphB4-RASA1 mutations, including the potential role of somatic mosaicism. These observations have potential diagnostic and therapeutic implications for patients with rare congenital cerebrovascular diseases and their families.

Exome Sequencing of a Primary Ovarian Insufficiency Cohort Reveals Common Molecular Etiologies for a Spectrum of Disease. - Jolly, Angad; Bayram, Yavuz; Turan, Serap; Aycan, Zehra; Tos, Tulay; Abali, Zehra Yavas; Hacihamdioglu, Bulent; Coban Akdemir, Zeynep Hande; Hijazi, Hadia; Bas, Serpil; Atay, Zeynep; Guran, Tulay; et al. (J Clin Endocrinol Metab, 2019)
CONTEXT: Primary ovarian insufficiency (POI) encompasses a spectrum of premature menopause, including both primary and secondary amenorrhea. For 75% to 90% of individuals with hypergonadotropic hypogonadism presenting as POI, the molecular etiology is unknown. Common etiologies include chromosomal abnormalities, environmental factors, and congenital disorders affecting ovarian development and function, as well as syndromic and nonsyndromic single gene disorders suggesting POI represents a complex trait. OBJECTIVE: To characterize the contribution of known disease genes to POI and identify molecular etiologies and biological underpinnings of POI. DESIGN, SETTING, AND PARTICIPANTS: We applied exome sequencing (ES) and family-based genomics to 42 affected female individuals from 36 unrelated Turkish families, including 31 with reported parental consanguinity. RESULTS: This analysis identified likely damaging, potentially contributing variants and molecular diagnoses in 16 families (44%), including 11 families with likely damaging variants in known genes and five families with predicted deleterious variants in disease genes (IGSF10, MND1, MRPS22, and SOHLH1) not previously associated with POI. Of the 16 families, 2 (13%) had evidence for potentially pathogenic variants at more than one locus. Absence of heterozygosity consistent with identity-by-descent mediated recessive disease burden contributes to molecular diagnosis in 15 of 16 (94%) families. GeneMatcher allowed identification of additional families from diverse genetic backgrounds. CONCLUSIONS: ES analysis of a POI cohort further characterized locus heterogeneity, reaffirmed the association of genes integral to meiotic recombination, demonstrated the likely contribution of genes involved in hypothalamic development, and documented multilocus pathogenic variation suggesting the potential for oligogenic inheritance contributing to the development of POI.

Exome sequencing of family trios from the National Birth Defects Prevention Study: Tapping into a rich resource of genetic and environmental data. - Jenkins, Mary M; Almli, Lynn M; Pangilinan, Faith; Chong, Jessica X; Blue, Elizabeth E; Shapira, Stuart K; White, Janson; McGoldrick, Daniel; Smith, Joshua D; Mullikin, James C; Bean, Christopher J; Nembhard, Wendy N; et al. (Birth Defects Res, 2019)
BACKGROUND: The National Birth Defects Prevention Study (NBDPS) is a multisite, population-based, case-control study of genetic and nongenetic risk factors for major structural birth defects. Eligible women had a pregnancy affected by a birth defect or a liveborn child without a birth defect between 1997 and 2011. They were invited to complete a telephone interview to collect pregnancy exposure data and were mailed buccal cell collection kits to collect specimens from themselves, their child (if living), and their child's father. Over 23,000 families representing more than 30 major structural birth defects provided DNA specimens. METHODS: To evaluate their utility for exome sequencing (ES), specimens from 20 children with colonic atresia were studied. Evaluations were conducted on specimens collected using cytobrushes stored and transported in open versus closed packaging, on native genomic DNA (gDNA) versus whole genome amplified (WGA) products and on a library preparation protocol adapted to low amounts of DNA. RESULTS: The DNA extracted from brushes in open packaging yielded higher quality sequence data than DNA from brushes in closed packaging. Quality metrics of sequenced gDNA were consistently higher than metrics from corresponding WGA products and were consistently high when using a low input protocol. CONCLUSIONS: This proof-of-principle study established conditions under which ES can be applied to NBDPS specimens. Successful sequencing of exomes from well-characterized NBDPS families indicated that this unique collection can be used to investigate the roles of genetic variation and gene-environment interaction effects in birth defect etiologies, providing a valuable resource for birth defect researchers.

Exome sequencing reveals a high prevalence of BRCA1 and BRCA2 founder variants in a diverse population-based biobank. - Abul-Husn, Noura S; Soper, Emily R; Odgis, Jacqueline A; Cullina, Sinead; Bobo, Dean; Moscati, Arden; Rodriguez, Jessica E; Loos, Ruth J F; Cho, Judy H; Belbin, Gillian M; Suckiel, Sabrina A; Kenny, Eimear E (Genome Med, 2019)
BACKGROUND: Pathogenic variants in BRCA1 and BRCA2 (BRCA1/2) lead to increased risk of breast, ovarian, and other cancers, but most variant-positive individuals in the general population are unaware of their risk, and little is known about prevalence in non-European populations. We investigated BRCA1/2 prevalence and impact in the electronic health record (EHR)-linked BioMe Biobank in New York City. METHODS: Exome sequence data from 30,223 adult BioMe participants were evaluated for pathogenic variants in BRCA1/2. Prevalence estimates were made in population groups defined by genetic ancestry and self-report. EHR data were used to evaluate clinical characteristics of variant-positive individuals. RESULTS: There were 218 (0.7%) individuals harboring expected pathogenic variants, resulting in an overall prevalence of 1 in 139. The highest prevalence was in individuals with Ashkenazi Jewish (AJ; 1 in 49), Filipino and other Southeast Asian (1 in 81), and non-AJ European (1 in 103) ancestry. Among 218 variant-positive individuals, 112 (51.4%) harbored known founder variants: 80 had AJ founder variants (BRCA1 c.5266dupC and c.68_69delAG, and BRCA2 c.5946delT), 8 had a Puerto Rican founder variant (BRCA2 c.3922G>T), and 24 had one of 19 other founder variants. Non-European populations were more likely to harbor BRCA1/2 variants that were not classified in ClinVar or that had uncertain or conflicting evidence for pathogenicity (uncertain/conflicting). Within mixed ancestry populations, such as Hispanic/Latinos with genetic ancestry from Africa, Europe, and the Americas, there was a strong correlation between the proportion of African genetic ancestry and the likelihood of harboring an uncertain/conflicting variant. Approximately 28% of variant-positive individuals had a personal history, and 45% had a personal or family history of BRCA1/2-associated cancers. Approximately 27% of variant-positive individuals had prior clinical genetic testing for BRCA1/2. However, individuals with AJ founder variants were twice as likely to have had a clinical test (39%) than those with other pathogenic variants (20%). CONCLUSIONS: These findings deepen our knowledge about BRCA1/2 variants and associated cancer risk in diverse populations, indicate a gap in knowledge about potential cancer-related variants in non-European populations, and suggest that genomic screening in diverse patient populations may be an effective tool to identify at-risk individuals.

The expanding phenotype of OFD1-related disorders: Hemizygous loss-of-function variants in three patients with primary ciliary dyskinesia. - Hannah, William B; DeBrosse, Suzanne; Kinghorn, BreAnna; Strausbaugh, Steven; Aitken, Moira L; Rosenfeld, Margaret; Wolf, Whitney E; Knowles, Michael R; Zariwala, Maimoona A (Mol Genet Genomic Med, 2019)
BACKGROUND: OFD1 has long been recognized as the gene implicated in the classic dysmorphology syndrome, oral-facial-digital syndrome type I (OFDSI). Over time, pathogenic variants in OFD1 were found to be associated with X-linked intellectual disability, Joubert syndrome type 10 (JBTS10), Simpson-Golabi-Behmel syndrome type 2 (SGBS2), and retinitis pigmentosa. Recently, OFD1 pathogenic variants have been implicated in primary ciliary dyskinesia (PCD), a disorder of the motile cilia with a phenotype that includes recurrent oto-sino-pulmonary infections, situs abnormalities, and decreased fertility. METHODS: We describe three male patients with PCD who were found to have hemizygous pathogenic variants in OFD1, further supporting that PCD is part of a clinical spectrum of OFD1-related disorders. In addition, we provide a review of the available clinical literature describing patients with OFD1 variants and highlight the phenotypic variability of OFD1-related disease. RESULTS: Some individuals with hemizygous OFD1 variants have PCD, either apparently isolated or in combination with other features of OFD1-related disorders. CONCLUSION: As clinicians consider the presence or absence of conditions allelic at OFD1, PCD should be considered part of the spectrum of OFD1-related disorders. Understanding the OFD1-related disease spectrum may allow for more focused genetic testing and more timely management of treatable sequelae.

Exploring by whole exome sequencing patients with initial diagnosis of Rubinstein-Taybi syndrome: the interconnections of epigenetic machinery disorders. - Negri, Gloria; Magini, Pamela; Milani, Donatella; Crippa, Milena; Biamino, Elisa; Piccione, Maria; Sotgiu, Stefano; Perrìa, Chiara; Vitiello, Giuseppina; Frontali, Marina; Boni, Antonella; Di Fede, Elisabetta; et al. (Hum Genet, 2019)
Rubinstein-Taybi syndrome (RSTS) is an autosomal-dominant neurodevelopmental disease affecting 1:125,000 newborns characterized by intellectual disability, growth retardation, facial dysmorphisms and skeletal abnormalities. RSTS is caused by mutations in genes encoding for writers of the epigenetic machinery: CREBBP (~ 60%) or its homologous EP300 (~ 10%). No causative mutation is identified in up to 30% of patients. We performed whole-exome sequencing (WES) on eight RSTS-like individuals who had normal high-resolution array CGH testing and were CREBBP- and EP300-mutation -negative, to identify the molecular cause. In four cases, we identified putatively causal variants in three genes (ASXL1, KMT2D and KMT2A) encoding members of the epigenetic machinery known to be associated with the Bohring-Opitz, Kabuki and Wiedemann-Steiner syndromes. Each variant is novel, de novo, fulfills the ACMG criteria and is predicted to result in loss-of-function leading to haploinsufficiency of the epi-gene. In two of the remaining cases, homozygous/compound heterozygous variants in XYLT2 and PLCB4 genes, respectively, associated with spondyloocular and auriculocondylar 2 syndromes and in the latter an additional candidate variant in XRN2, a gene yet unrelated to any disease, were detected, but their pathogenicity remains uncertain. These results underscore the broad clinical spectrum of Mendelian disorders of the epigenetic apparatus and the high rate of WES disclosure of the genetic basis in cases which may pose a challenge for phenotype encompassing distinct syndromes. The overlapping features of distinct intellectual disability syndromes reflect common pathogenic molecular mechanisms affecting the complex regulation of balance between open and closed chromatin.
Keywords: Child; Child, Preschool; Comparative Genomic Hybridization; CREB-Binding Protein; E1A-Associated p300 Protein; Epigenesis, Genetic; Facies; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mutation; Phenotype; Rubinstein-Taybi Syndrome; Whole Exome Sequencing

FAM92A Underlies Nonsyndromic Postaxial Polydactyly in Humans and an Abnormal Limb and Digit Skeletal Phenotype in Mice. - Schrauwen, Isabelle; Giese, Arnaud Pj; Aziz, Abdul; Lafont, David Tino; Chakchouk, Imen; Santos-Cortez, Regie Lyn P; Lee, Kwanghyuk; Acharya, Anushree; Khan, Falak Sher; Ullah, Asmat; Nickerson, Deborah A; Bamshad, Michael J; et al. (J Bone Miner Res, 2019)
Polydactyly is a common congenital anomaly of the hand and foot. Postaxial polydactyly (PAP) is characterized by one or more posterior or postaxial digits. In a Pakistani family with autosomal recessive nonsyndromic postaxial polydactyly type A (PAPA), we performed genomewide genotyping, linkage analysis, and exome and Sanger sequencing. Exome sequencing revealed a homozygous nonsense variant (c.478C>T, p.[Arg160*]) in the FAM92A gene within the mapped region on 8q21.13-q24.12 that segregated with the PAPA phenotype. We found that FAM92A is expressed in the developing mouse limb and E11.5 limb bud including the progress zone and the apical ectodermal ridge, where it strongly localizes at the cilia level, suggesting an important role in limb patterning. The identified variant leads to a loss of the FAM92A/Chibby1 complex that is crucial for ciliogenesis and impairs the recruitment and the colocalization of FAM92A with Chibby1 at the base of the cilia. In addition, we show that Fam92a homozygous mice also exhibit an abnormal digit morphology, including metatarsal osteomas and polysyndactyly, in addition to distinct abnormalities on the deltoid tuberosity of their humeri. In conclusion, we present a new nonsyndromic PAPA ciliopathy due to a loss-of-function variant in FAM92A. © 2018 American Society for Bone and Mineral Research.

Genetic architecture of laterality defects revealed by whole exome sequencing. - Li, Alexander H; Hanchard, Neil A; Azamian, Mahshid; D'Alessandro, Lisa C A; Coban-Akdemir, Zeynep; Lopez, Keila N; Hall, Nancy J; Dickerson, Heather; Nicosia, Annarita; Fernbach, Susan; Boone, Philip M; Gambin, Tomaz; et al. (Eur J Hum Genet, 2019)
Aberrant left-right patterning in the developing human embryo can lead to a broad spectrum of congenital malformations. The causes of most laterality defects are not known, with variants in established genes accounting for <20% of cases. We sought to characterize the genetic spectrum of these conditions by performing whole-exome sequencing of 323 unrelated laterality cases. We investigated the role of rare, predicted-damaging variation in 1726 putative laterality candidate genes derived from model organisms, pathway analyses, and human phenotypes. We also evaluated the contribution of homo/hemizygous exon deletions and gene-based burden of rare variation. A total of 28 candidate variants (26 rare predicted-damaging variants and 2 hemizygous deletions) were identified, including variants in genes known to cause heterotaxy and primary ciliary dyskinesia (ACVR2B, NODAL, ZIC3, DNAI1, DNAH5, HYDIN, MMP21), and genes without a human phenotype association, but with prior evidence for a role in embryonic laterality or cardiac development. Sanger validation of the latter variants in probands and their parents revealed no de novo variants, but apparent transmitted heterozygous (ROCK2, ISL1, SMAD2), and hemizygous (RAI2, RIPPLY1) variant patterns. Collectively, these variants account for 7.1% of our study subjects. We also observe evidence for an excess burden of rare, predicted loss-of-function variation in PXDNL and BMS1- two genes relevant to the broader laterality phenotype. These findings highlight potential new genes in the development of laterality defects, and suggest extensive locus heterogeneity and complex genetic models in this class of birth defects.

Genetic diagnosis in first or second trimester pregnancy loss using exome sequencing: a systematic review of human essential genes. - Robbins, Sarah M; Thimm, Matthew A; Valle, David; Jelin, Angie C (J Assist Reprod Genet, 2019)
PURPOSE: Non-aneuploid recurrent pregnancy loss (RPL) affects approximately 100,000 pregnancies worldwide annually. Exome sequencing (ES) may help uncover the genetic etiology of RPL and, more generally, pregnancy loss as a whole. Previous studies have attempted to predict the genes that, when disrupted, may cause human embryonic lethality. However, predictions by these early studies rarely point to the same genes. Case reports of pathogenic variants identified in RPL cases offer another clue. We evaluated known genetic etiologies of RPL identified by ES. METHODS: We gathered primary research articles from PubMed and Embase involving case reports of RPL reporting variants identified by ES. Two authors independently reviewed all articles for eligibility and extracted data based on predetermined criteria. Preliminary and amended analysis isolated 380 articles; 15 met all inclusion criteria. RESULTS: These 15 articles described 74 families with 279 reported RPLs with 34 candidate pathogenic variants in 19 genes (NOP14, FOXP3, APAF1, CASP9, CHRNA1, NLRP5, MMP10, FGA, FLT1, EPAS1, IDO2, STIL, DYNC2H1, IFT122, PADI6, CAPS, MUSK, NLRP2, NLRP7) and 26 variants of unknown significance in 25 genes. These genes cluster in four essential pathways: (1) gene expression, (2) embryonic development, (3) mitosis and cell cycle progression, and (4) inflammation and immunity. CONCLUSIONS: For future studies of RPL, we recommend trio-based ES in cases with normal parental karyotypes. In vitro fertilization with preimplantation genetic diagnosis can be pursued if causative variants are found. Utilization of other sequencing technologies in concert with ES should improve understanding of the causes of early embryonic lethality in humans.

The Genetic Landscape of Diamond-Blackfan Anemia. - Ulirsch, Jacob C; Verboon, Jeffrey M; Kazerounian, Shideh; Guo, Michael H; Yuan, Daniel; Ludwig, Leif S; Handsaker, Robert E; Abdulhay, Nour J; Fiorini, Claudia; Genovese, Giulio; Lim, Elaine T; Cheng, Aaron; et al. (Am J Hum Genet, 2019)

Genetic regulatory variation in populations informs transcriptome analysis in rare disease. - Mohammadi, Pejman; Castel, Stephane E; Cummings, Beryl B; Einson, Jonah; Sousa, Christina; Hoffman, Paul; Donkervoort, Sandra; Jiang, Zhuoxun; Mohassel, Payam; Foley, A Reghan; Wheeler, Heather E; Im, Hae Kyung; et al. (Science, 2019)
Transcriptome data can facilitate the interpretation of the effects of rare genetic variants. Here, we introduce ANEVA (analysis of expression variation) to quantify genetic variation in gene dosage from allelic expression (AE) data in a population. Application of ANEVA to the Genotype-Tissues Expression (GTEx) data showed that this variance estimate is robust and correlated with selective constraint in a gene. Using these variance estimates in a dosage outlier test (ANEVA-DOT) applied to AE data from 70 Mendelian muscular disease patients showed accuracy in detecting genes with pathogenic variants in previously resolved cases and led to one confirmed and several potential new diagnoses. Using our reference estimates from GTEx data, ANEVA-DOT can be incorporated in rare disease diagnostic pipelines to use RNA-sequencing data more effectively.

Genetic variants in the LAMA5 gene in pediatric nephrotic syndrome. - Braun, Daniela A; Warejko, Jillian K; Ashraf, Shazia; Tan, Weizhen; Daga, Ankana; Schneider, Ronen; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; Majmundar, Amar J; Nakayama, Makiko; Schapiro, David; et al. (Nephrol Dial Transplant, 2019)
BACKGROUND: Nephrotic syndrome (NS), a chronic kidney disease, is characterized by significant loss of protein in the urine causing hypoalbuminemia and edema. In general, ∼15% of childhood-onset cases do not respond to steroid therapy and are classified as steroid-resistant NS (SRNS). In ∼30% of cases with SRNS, a causative mutation can be detected in one of 44 monogenic SRNS genes. The gene LAMA5 encodes laminin-α5, an essential component of the glomerular basement membrane. Mice with a hypomorphic mutation in the orthologous gene Lama5 develop proteinuria and hematuria. METHODS: To identify additional monogenic causes of NS, we performed whole exome sequencing in 300 families with pediatric NS. In consanguineous families we applied homozygosity mapping to identify genomic candidate loci for the underlying recessive mutation. RESULTS: In three families, in whom mutations in known NS genes were excluded, but in whom a recessive, monogenic cause of NS was strongly suspected based on pedigree information, we identified homozygous variants of unknown significance (VUS) in the gene LAMA5. While all affected individuals had nonsyndromic NS with an early onset of disease, their clinical outcome and response to immunosuppressive therapy differed notably. CONCLUSION: We here identify recessive VUS in the gene LAMA5 in patients with partially treatment-responsive NS. More data will be needed to determine the impact of these VUS in disease management. However, familial occurrence of disease, data from genetic mapping and a mouse model that recapitulates the NS phenotypes suggest that these genetic variants may be inherited factors that contribute to the development of NS in pediatric patients.

Genome sequencing identifies multiple deleterious variants in autism patients with more severe phenotypes. - Guo, Hui; Duyzend, Michael H; Coe, Bradley P; Baker, Carl; Hoekzema, Kendra; Gerdts, Jennifer; Turner, Tychele N; Zody, Michael C; Beighley, Jennifer S; Murali, Shwetha C; Nelson, Bradley J; Bamshad, Michael J; et al. (Genet Med, 2019)
PURPOSE: To maximize the discovery of potentially pathogenic variants to better understand the diagnostic utility of genome sequencing (GS) and to assess how the presence of multiple risk events might affect the phenotypic severity in autism spectrum disorders (ASD). METHODS: GS was applied to 180 simplex and multiplex ASD families (578 individuals, 213 patients) with exome sequencing and array comparative genomic hybridization further applied to a subset for validation and cross-platform comparisons. RESULTS: We found that 40.8% of patients carried variants with evidence of disease risk, including a de novo frameshift variant in NR4A2 and two de novo missense variants in SYNCRIP, while 21.1% carried clinically relevant pathogenic or likely pathogenic variants. Patients with more than one risk variant (9.9%) were more severely affected with respect to cognitive ability compared with patients with a single or no-risk variant. We observed no instance among the 27 multiplex families where a pathogenic or likely pathogenic variant was transmitted to all affected members in the family. CONCLUSION: The study demonstrates the diagnostic utility of GS, especially for multiple risk variants that contribute to the phenotypic severity, shows the genetic heterogeneity in multiplex families, and provides evidence for new genes for follow up.

Genome Sequencing Identifies the Pathogenic Variant Missed by Prior Testing in an Infant with Marfan Syndrome. - Wojcik, Monica H; Thiele, Katri; Grant, Carly F; Chao, Katherine; Goodrich, Julia; O'Donnell-Luria, Anne; Lacro, Ronald V; Tan, Wen-Hann; Agrawal, Pankaj B (J Pediatr, 2019)
We describe an infant with a phenotype typical of early onset Marfan syndrome whose genetic evaluation, including Sanger sequencing and deletion/duplication testing of FBN1 and exome sequencing, was negative. Ultimately, genome sequencing revealed a deletion missed on prior testing, demonstrating the unique utility of genome sequencing for molecular genetic diagnosis.

The Genomics of Arthrogryposis, a Complex Trait: Candidate Genes and Further Evidence for Oligogenic Inheritance. - Pehlivan, Davut; Bayram, Yavuz; Gunes, Nilay; Coban Akdemir, Zeynep; Shukla, Anju; Bierhals, Tatjana; Tabakci, Burcu; Sahin, Yavuz; Gezdirici, Alper; Fatih, Jawid M; Gulec, Elif Yilmaz; Yesil, Gözde; et al. (Am J Hum Genet, 2019)
Arthrogryposis is a clinical finding that is present either as a feature of a neuromuscular condition or as part of a systemic disease in over 400 Mendelian conditions. The underlying molecular etiology remains largely unknown because of genetic and phenotypic heterogeneity. We applied exome sequencing (ES) in a cohort of 89 families with the clinical sign of arthrogryposis. Additional molecular techniques including array comparative genomic hybridization (aCGH) and Droplet Digital PCR (ddPCR) were performed on individuals who were found to have pathogenic copy number variants (CNVs) and mosaicism, respectively. A molecular diagnosis was established in 65.2% (58/89) of families. Eleven out of 58 families (19.0%) showed evidence for potential involvement of pathogenic variation at more than one locus, probably driven by absence of heterozygosity (AOH) burden due to identity-by-descent (IBD). RYR3, MYOM2, ERGIC1, SPTBN4, and ABCA7 represent genes, identified in two or more families, for which mutations are probably causative for arthrogryposis. We also provide evidence for the involvement of CNVs in the etiology of arthrogryposis and for the idea that both mono-allelic and bi-allelic variants in the same gene cause either similar or distinct syndromes. We were able to identify the molecular etiology in nine out of 20 families who underwent reanalysis. In summary, our data from family-based ES further delineate the molecular etiology of arthrogryposis, yielded several candidate disease-associated genes, and provide evidence for mutational burden in a biological pathway or network. Our study also highlights the importance of reanalysis of individuals with unsolved diagnoses in conjunction with sequencing extended family members.

GGC Repeat Expansion and Exon 1 Methylation of XYLT1 Is a Common Pathogenic Variant in Baratela-Scott Syndrome. - LaCroix, Amy J; Stabley, Deborah; Sahraoui, Rebecca; Adam, Margaret P; Mehaffey, Michele; Kernan, Kelly; Myers, Candace T; Fagerstrom, Carrie; Anadiotis, George; Akkari, Yassmine M; Robbins, Katherine M; Gripp, Karen W; et al. (Am J Hum Genet, 2019)
Baratela-Scott syndrome (BSS) is a rare, autosomal-recessive disorder characterized by short stature, facial dysmorphisms, developmental delay, and skeletal dysplasia caused by pathogenic variants in XYLT1. We report clinical and molecular investigation of 10 families (12 individuals) with BSS. Standard sequencing methods identified biallelic pathogenic variants in XYLT1 in only two families. Of the remaining cohort, two probands had no variants and six probands had only a single variant, including four with a heterozygous 3.1 Mb 16p13 deletion encompassing XYLT1 and two with a heterozygous truncating variant. Bisulfite sequencing revealed aberrant hypermethylation in exon 1 of XYLT1, always in trans with the sequence variant or deletion when present; both alleles were methylated in those with no identified variant. Expression of the methylated XYLT1 allele was severely reduced in fibroblasts from two probands. Southern blot studies combined with repeat expansion analysis of genome sequence data showed that the hypermethylation is associated with expansion of a GGC repeat in the XYLT1 promoter region that is not present in the reference genome, confirming that BSS is a trinucleotide repeat expansion disorder. The hypermethylated allele accounts for 50% of disease alleles in our cohort and is not present in 130 control subjects. Our study highlights the importance of investigating non-sequence-based alterations, including epigenetic changes, to identify the missing heritability in genetic disorders.

Global genetic insight contributed by consanguineous Pakistani families segregating hearing loss. - Richard, Elodie M; Santos-Cortez, Regie Lyn P; Faridi, Rabia; Rehman, Atteeq U; Lee, Kwanghyuk; Shahzad, Mohsin; Acharya, Anushree; Khan, Asma A; Imtiaz, Ayesha; Chakchouk, Imen; Takla, Christina; Abbe, Izoduwa; et al. (Hum Mutat, 2019)
Consanguineous Pakistani pedigrees segregating deafness have contributed decisively to the discovery of 31 of the 68 genes associated with nonsyndromic autosomal recessive hearing loss (HL) worldwide. In this study, we utilized genome-wide genotyping, Sanger and exome sequencing to identify 163 DNA variants in 41 previously reported HL genes segregating in 321 Pakistani families. Of these, 70 (42.9%) variants identified in 29 genes are novel. As expected from genetic studies of disorders segregating in consanguineous families, the majority of affected individuals (94.4%) are homozygous for HL-associated variants, with the other variants being compound heterozygotes. The five most common HL genes in the Pakistani population are SLC26A4, MYO7A, GJB2, CIB2 and HGF, respectively. Our study provides a profile of the genetic etiology of HL in Pakistani families, which will allow for the development of more efficient genetic diagnostic tools, aid in accurate genetic counseling, and guide application of future gene-based therapies. These findings are also valuable in interpreting pathogenicity of variants that are potentially associated with HL in individuals of all ancestries. The Pakistani population, and its infrastructure for studying human genetics, will continue to be valuable to gene discovery for HL and other inherited disorders.

Hearing impairment locus heterogeneity and identification of PLS1 as a new autosomal dominant gene in Hungarian Roma. - Schrauwen, Isabelle; Melegh, Béla I; Chakchouk, Imen; Acharya, Anushree; Nasir, Abdul; Poston, Alexis; Cornejo-Sanchez, Diana M; Szabo, Zsolt; Karosi, Tamás; Bene, Judit; Melegh, Béla; Leal, Suzanne M (Eur J Hum Genet, 2019)
Roma are a socially and culturally distinct isolated population with genetically divergent subisolates, residing mainly across Central, Southern, and Eastern Europe. We evaluated the genetic etiology of hearing impairment (HI) in 15 Hungarian Roma families through exome sequencing. A family with autosomal dominant non-syndromic HI segregating a rare variant in the Calponin-homology 2 domain of PLS1, or Plastin 1 [p.(Leu363Phe)] was identified. Young adult Pls1 knockout mice have progressive HI and show morphological defects to their inner hair cells. There is evidence that PLS1 is important in the preservation of adult stereocilia and normal hearing. Four families segregated the European ancestral variant c.35delG [p.(Gly12fs)] in GJB2, and one family was homozygous for p.(Trp24*), an Indian subcontinent ancestral variant which is common amongst Roma from Slovakia, Czech Republic, and Spain. We also observed variants in known HI genes USH1G, USH2A, MYH9, MYO7A, and a splice site variant in MANBA (c.2158-2A>G) in a family with HI, intellectual disability, behavioral problems, and respiratory inflammation, which was previously reported in a Czech Roma family with similar features. Lastly, using multidimensional scaling and ADMIXTURE analyses, we delineate the degree of Asian/European admixture in the HI families understudy, and show that Roma individuals carrying the GJB2 p.(Trp24*) and MANBA c.2158-2A>G variants have a more pronounced South Asian background, whereas the other hearing-impaired Roma display an ancestral background similar to Europeans. We demonstrate a diverse genetic HI etiology in the Hungarian Roma and identify a new gene PLS1, for autosomal dominant human non-syndromic HI.

Heterozygosity mapping for human dominant trait variants. - Imai-Okazaki, Atsuko; Li, Yi; Horpaopan, Sukanya; Riazalhosseini, Yasser; Garshasbi, Masoud; Mosse, Yael P; Zhang, Di; Schrauwen, Isabelle; Sharma, Aarushi; Fann, Cathy S J; Leal, Suzanne M; Lathrop, Mark; et al. (Hum Mutat, 2019)
Homozygosity mapping is a well-known technique to identify runs of homozygous variants that are likely to harbor genes responsible for autosomal recessive disease, but a comparable method for autosomal dominant traits has been lacking. We developed an approach to map dominant disease genes based on heterozygosity frequencies of sequence variants in the immediate vicinity of a dominant trait. We demonstrate through theoretical analysis that DNA variants surrounding an inherited dominant disease variant tend to have increased heterozygosity compared with variants elsewhere in the genome. We confirm existence of this phenomenon in sequence data with known dominant pathogenic variants obtained on family members and in unrelated population controls. A computer-based approach to estimating empirical significance levels associated with our test statistics shows genome-wide p-values smaller than 0.05 for many but not all of the individuals carrying a pathogenic variant.

Heterozygous CTNNB1 and TBX4 variants in a patient with abnormal lung growth, pulmonary hypertension, microcephaly, and spasticity. - Karolak, Justyna A; Szafranski, Przemyslaw; Kilner, David; Patel, Chirag; Scurry, Bonnie; Kinning, Esther; Chandler, Kate; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Lupski, James R; Popek, Edwina; Stankiewicz, Paweł (Clin Genet, 2019)
The canonical wingless (Wnt) and fibroblast growth factor (FGF) signaling pathways involving CTNNB1 and TBX4, respectively, are crucial for the regulation of human development. Perturbations of these pathways and disruptions from biological homeostasis have been associated with abnormal morphogenesis of multiple organs, including the lung. The aim of this study was to identify the underlying genetic cause of abnormal lung growth, pulmonary hypertension (PAH), severe microcephaly, and muscle spasticity in a full-term newborn, who died at 4 months of age due to progressively worsening PAH and respiratory failure. Family trio exome sequencing showed a de novo heterozygous nonsense c.1603C>T (p.Arg535*) variant in CTNNB1 and a paternally inherited heterozygous missense c.1198G>A (p.Glu400Lys) variant in TBX4, both predicted to be likely deleterious. We expand the phenotypic spectrum associated with CTNNB1 and TBX4 variants and indicate that they could act synergistically to produce a distinct more severe phenotype. Our findings further support a recently proposed complex compound inheritance model in lethal lung developmental diseases and the contention that dual molecular diagnoses can parsimoniously explain blended phenotypes.

Heterozygous Variants in KMT2E Cause a Spectrum of Neurodevelopmental Disorders and Epilepsy. - O'Donnell-Luria, Anne H; Pais, Lynn S; Faundes, Víctor; Wood, Jordan C; Sveden, Abigail; Luria, Victor; Abou Jamra, Rami; Accogli, Andrea; Amburgey, Kimberly; Anderlid, Britt Marie; Azzarello-Burri, Silvia; Basinger, Alice A; et al. (Am J Hum Genet, 2019)
We delineate a KMT2E-related neurodevelopmental disorder on the basis of 38 individuals in 36 families. This study includes 31 distinct heterozygous variants in KMT2E (28 ascertained from Matchmaker Exchange and three previously reported), and four individuals with chromosome 7q22.2-22.23 microdeletions encompassing KMT2E (one previously reported). Almost all variants occurred de novo, and most were truncating. Most affected individuals with protein-truncating variants presented with mild intellectual disability. One-quarter of individuals met criteria for autism. Additional common features include macrocephaly, hypotonia, functional gastrointestinal abnormalities, and a subtle facial gestalt. Epilepsy was present in about one-fifth of individuals with truncating variants and was responsive to treatment with anti-epileptic medications in almost all. More than 70% of the individuals were male, and expressivity was variable by sex; epilepsy was more common in females and autism more common in males. The four individuals with microdeletions encompassing KMT2E generally presented similarly to those with truncating variants, but the degree of developmental delay was greater. The group of four individuals with missense variants in KMT2E presented with the most severe developmental delays. Epilepsy was present in all individuals with missense variants, often manifesting as treatment-resistant infantile epileptic encephalopathy. Microcephaly was also common in this group. Haploinsufficiency versus gain-of-function or dominant-negative effects specific to these missense variants in KMT2E might explain this divergence in phenotype, but requires independent validation. Disruptive variants in KMT2E are an under-recognized cause of neurodevelopmental abnormalities.

Homozygous Missense Variants in NTNG2, Encoding a Presynaptic Netrin-G2 Adhesion Protein, Lead to a Distinct Neurodevelopmental Disorder. - Dias, Caroline M; Punetha, Jaya; Zheng, Céline; Mazaheri, Neda; Rad, Abolfazl; Efthymiou, Stephanie; Petersen, Andrea; Dehghani, Mohammadreza; Pehlivan, Davut; Partlow, Jennifer N; Posey, Jennifer E; Salpietro, Vincenzo; et al. (Am J Hum Genet, 2019)
NTNG2 encodes netrin-G2, a membrane-anchored protein implicated in the molecular organization of neuronal circuitry and synaptic organization and diversification in vertebrates. In this study, through a combination of exome sequencing and autozygosity mapping, we have identified 16 individuals (from seven unrelated families) with ultra-rare homozygous missense variants in NTNG2; these individuals present with shared features of a neurodevelopmental disorder consisting of global developmental delay, severe to profound intellectual disability, muscle weakness and abnormal tone, autistic features, behavioral abnormalities, and variable dysmorphisms. The variants disrupt highly conserved residues across the protein. Functional experiments, including in silico analysis of the protein structure, in vitro assessment of cell surface expression, and in vitro knockdown, revealed potential mechanisms of pathogenicity of the variants, including loss of protein function and decreased neurite outgrowth. Our data indicate that appropriate expression of NTNG2 plays an important role in neurotypical development.

Homozygous noncanonical splice variant in in two siblings with multiple congenital anomalies and global developmental delay. - Okur, Volkan; LeDuc, Charles A; Guzman, Edwin; Valivullah, Zaheer M; Anyane-Yeboa, Kwame; Chung, Wendy K (Cold Spring Harb Mol Case Stud, 2019)
Two siblings, one male and one female, ages 6 and 13 yr old, have similar clinical features of global developmental delay, multiple congenital anomalies affecting the cardiac, genitourinary, and skeletal systems, and abnormal eye movements. Whole-genome sequencing revealed a homozygous splice variant (NM_014462.3:c.231+4A>C) in that segregated with the phenotype in the family. LSM1 has a role in pre-mRNA splicing and degradation. Expression studies revealed absence of expression of the canonical isoform in the affected individuals. The knockout mice have a partially overlapping phenotype that affects the brain, heart, and eye. To our knowledge, has not been associated with any human disorder; however, the tissue expression pattern, gene constraint, and the similarity of the phenotype in our patients and the knockout mice models suggest it has a role in the development of multiple organ systems in humans.

Hypomorphic caspase activation and recruitment domain 11 (CARD11) mutations associated with diverse immunologic phenotypes with or without atopic disease. - Dorjbal, Batsukh; Stinson, Jeffrey R; Ma, Chi A; Weinreich, Michael A; Miraghazadeh, Bahar; Hartberger, Julia M; Frey-Jakobs, Stefanie; Weidinger, Stephan; Moebus, Lena; Franke, Andre; Schäffer, Alejandro A; Bulashevska, Alla; et al. (J Allergy Clin Immunol, 2019)
BACKGROUND: Caspase activation and recruitment domain 11 (CARD11) encodes a scaffold protein in lymphocytes that links antigen receptor engagement with downstream signaling to nuclear factor κB, c-Jun N-terminal kinase, and mechanistic target of rapamycin complex 1. Germline CARD11 mutations cause several distinct primary immune disorders in human subjects, including severe combined immune deficiency (biallelic null mutations), B-cell expansion with nuclear factor κB and T-cell anergy (heterozygous, gain-of-function mutations), and severe atopic disease (loss-of-function, heterozygous, dominant interfering mutations), which has focused attention on CARD11 mutations discovered by using whole-exome sequencing. OBJECTIVES: We sought to determine the molecular actions of an extended allelic series of CARD11 and to characterize the expanding range of clinical phenotypes associated with heterozygous CARD11 loss-of-function alleles. METHODS: Cell transfections and primary T-cell assays were used to evaluate signaling and function of CARD11 variants. RESULTS: Here we report on an expanded cohort of patients harboring novel heterozygous CARD11 mutations that extend beyond atopy to include other immunologic phenotypes not previously associated with CARD11 mutations. In addition to (and sometimes excluding) severe atopy, heterozygous missense and indel mutations in CARD11 presented with immunologic phenotypes similar to those observed in signal transducer and activator of transcription 3 loss of function, dedicator of cytokinesis 8 deficiency, common variable immunodeficiency, neutropenia, and immune dysregulation, polyendocrinopathy, enteropathy, X-linked-like syndrome. Pathogenic variants exhibited dominant negative activity and were largely confined to the CARD or coiled-coil domains of the CARD11 protein. CONCLUSION: These results illuminate a broader phenotypic spectrum associated with CARD11 mutations in human subjects and underscore the need for functional studies to demonstrate that rare gene variants encountered in expected and unexpected phenotypes must nonetheless be validated for pathogenic activity.

Identification and association of recurrent ALOXE3 mutation with non-bullous congenital ichthyosiform erythroderma in two ethnically distinct Pakistani families. - Rahman, Simeen Ber; Mir, Asif; Ahmad, Nafees; Haider, Syed Husnain; Malik, Salman Akbar; Nasir, Muhammad (Congenit Anom (Kyoto), 2019)
Non-bullous congenital ichthyosiform erythroderma (NCIE) is characterized by skin scaling with erythema. In this study, two Pakistani families with NCIE are genetically characterized through Whole Exome and Sanger sequencing to identify molecular basis of the disease. We identified a nonsense homozygous c.2026C>T mutation of ALOXE3, causing premature termination of the eLOX3 protein (p.Q676X). In silico studies predicted impaired enzymatic activity of the premature truncated eLOX3, leading to abnormal synthesis of specific hepoxilin derivatives, essential for epidermal barrier formation. It is the first ever study reporting homozygotes of p.Q676X mutation in ethnically distinct two Pakistani families; otherwise, heterozygotes of the said mutation have been reported in South Asian population only. Hence, mutation seems to be region-specific and may be useful for molecular diagnosis of NCIE. Moreover, our findings should help in genetic counseling and career screening.
Keywords: 8,11,14-Eicosatrienoic Acid; Adolescent; Adult; Base Sequence; Case-Control Studies; Child; Child, Preschool; Codon, Nonsense; Ethnic Groups; Female; Flavanones; Gene Expression; Homozygote; Humans; Ichthyosis, Lamellar; Lipoxygenase; Male; Middle Aged; Molecular Docking Simulation; Pakistan; Pedigree; Protein Binding; Protein Structure, Secondary; Skin; Whole Exome Sequencing

Identification and therapeutic rescue of autophagosome and glutamate receptor defects in C9ORF72 and sporadic ALS neurons. - Shi, Yingxiao; Hung, Shu-Ting; Rocha, Gabriel; Lin, Shaoyu; Linares, Gabriel R; Staats, Kim A; Seah, Carina; Wang, Yaoming; Chickering, Michael; Lai, Jesse; Sugawara, Tohru; Sagare, Abhay P; et al. (JCI Insight, 2019)
Amyotrophic lateral sclerosis (ALS) is a fatal motor neuron disease with diverse etiologies. Therefore, the identification of common disease mechanisms and therapeutics targeting these mechanisms could dramatically improve clinical outcomes. To this end, we developed induced motor neuron (iMN) models from C9ORF72 and sporadic ALS (sALS) patients to identify targets that are effective against these types of cases, which together comprise ~90% of patients. We find that iMNs from C9ORF72 and several sporadic ALS patients share two common defects - impaired autophagosome formation and the aberrant accumulation of glutamate receptors. Moreover, we show that an anticoagulation-deficient form of activated protein C, 3K3A-APC, rescues these defects in both C9ORF72 and sporadic ALS iMNs. As a result, 3K3A-APC treatment lowers C9ORF72 dipeptide repeat protein (DPR) levels, restores nuclear TDP-43 localization, and rescues the survival of both C9ORF72 and sporadic ALS iMNs. Importantly, 3K3A-APC also lowers glutamate receptor levels and rescues proteostasis in vivo in C9ORF72 gain- and loss-of-function mouse models. Thus, motor neurons from C9ORF72 and at least a subset of sporadic ALS patients share common, early defects in autophagosome formation and glutamate receptor homeostasis and a single therapeutic approach may be efficacious against these disease processes.

Identification of CACNA1D variants associated with sinoatrial node dysfunction and deafness in additional Pakistani families reveals a clinical significance. - Liaqat, Khurram; Schrauwen, Isabelle; Raza, Syed Irfan; Lee, Kwanghyuk; Hussain, Shabir; Chakchouk, Imen; Nasir, Abdul; Acharya, Anushree; Abbe, Izoduwa; Umair, Muhammad; Ansar, Muhammad; Ullah, Irfan; et al. (J Hum Genet, 2019)
Sinoatrial node dysfunction and deafness (SANDD) syndrome is rare and characterized by a low heart beat and severe-to-profound deafness. Additional features include fatigue, dizziness, and episodic syncope. The sinoatrial node (SAN) drives heart automaticity and continuously regulates heart rate. The CACNA1D gene encoding the Ca1.3 protein expressed in inner hair cells, atria and SAN, induces loss-of-function in channel activity and underlies SANDD. To date, only one variant c.1208_1209insGGG:p.(G403_V404insG) has been reported for SANDD syndrome. We studied five Pakistani families with SANDD and characterized a new missense variant p.(A376V) in CACNA1D in one family, and further characterized the founder variant p.(G403_V404insG) in four additional pedigrees. We show that affected individuals in the four families which segregate p.(G403_V404insG) share a 1.03 MB haplotype on 3p21.1 suggesting they share a common distant ancestor. In conclusion, we identified new and known variants in CACNA1D in five Pakistani families with SANDD. This study is of clinical importance as the CACNA1D founder variant is only observed in families from the Khyber Pakhtunkhwa (KPK) province, in Pakistan. Therefore, screening patients with congenital deafness for SAN dysfunction in this province could ensure adequate follow-up and prevent cardiac failure associated with SAN.
Keywords: Adolescent; Calcium Channels, L-Type; Deafness; Female; Heart Diseases; Humans; Male; Mutation; Pakistan; Pedigree; Prognosis; Sinoatrial Node

Infant mortality: the contribution of genetic disorders. - Wojcik, Monica H; Schwartz, Talia S; Thiele, Katri E; Paterson, Heather; Stadelmaier, Rachel; Mullen, Thomas E; VanNoy, Grace E; Genetti, Casie A; Madden, Jill A; Gubbels, Cynthia S; Yu, Timothy W; Tan, Wen-Hann; et al. (J Perinatol, 2019)
OBJECTIVE: To determine the proportion of infant deaths occurring in the setting of a confirmed genetic disorder. STUDY DESIGN: A retrospective analysis of the electronic medical records of infants born from 1 January, 2011 to 1 June, 2017, who died prior to 1 year of age. RESULTS: Five hundred and seventy three deceased infants were identified. One hundred and seventeen were confirmed to have a molecular or cytogenetic diagnosis in a clinical diagnostic laboratory and an additional seven were diagnosed by research testing for a total of 124/573 (22%) diagnosed infants. A total of 67/124 (54%) had chromosomal disorders and 58/124 (47%) had single gene disorders (one infant had both). The proportion of diagnoses made by sequencing technologies, such as exome sequencing, increased over the years. CONCLUSIONS: The prevalence of confirmed genetic disorders within our cohort of infant deaths is higher than that previously reported. Increased efforts are needed to further understand the mortality burden of genetic disorders in infancy.

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States; Whole Exome Sequencing

Interchromosomal template-switching as a novel molecular mechanism for imprinting perturbations associated with Temple syndrome. - Carvalho, Claudia M B; Coban-Akdemir, Zeynep; Hijazi, Hadia; Yuan, Bo; Pendleton, Matthew; Harrington, Eoghan; Beaulaurier, John; Juul, Sissel; Turner, Daniel J; Kanchi, Rupa S; Jhangiani, Shalini N; Muzny, Donna M; et al. (Genome Med, 2019)
BACKGROUND: Intrachromosomal triplications (TRP) can contribute to disease etiology via gene dosage effects, gene disruption, position effects, or fusion gene formation. Recently, post-zygotic de novo triplications adjacent to copy-number neutral genomic intervals with runs of homozygosity (ROH) have been shown to result in uniparental isodisomy (UPD). The genomic structure of these complex genomic rearrangements (CGRs) shows a consistent pattern of an inverted triplication flanked by duplications (DUP-TRP/INV-DUP) formed by an iterative DNA replisome template-switching mechanism during replicative repair of a single-ended, double-stranded DNA (seDNA), the ROH results from an interhomolog or nonsister chromatid template switch. It has been postulated that these CGRs may lead to genetic abnormalities in carriers due to dosage-sensitive genes mapping within the copy-number variant regions, homozygosity for alleles at a locus causing an autosomal recessive (AR) disease trait within the ROH region, or imprinting-associated diseases. METHODS: Here, we report a family wherein the affected subject carries a de novo 2.2-Mb TRP followed by 42.2 Mb of ROH and manifests clinical features overlapping with those observed in association with chromosome 14 maternal UPD (UPD(14)mat). UPD(14)mat can cause clinical phenotypic features enabling a diagnosis of Temple syndrome. This CGR was then molecularly characterized by high-density custom aCGH, genome-wide single-nucleotide polymorphism (SNP) and methylation arrays, exome sequencing (ES), and the Oxford Nanopore long-read sequencing technology. RESULTS: We confirmed the postulated DUP-TRP/INV-DUP structure by multiple orthogonal genomic technologies in the proband. The methylation status of known differentially methylated regions (DMRs) on chromosome 14 revealed that the subject shows the typical methylation pattern of UPD(14)mat. Consistent with these molecular findings, the clinical features overlap with those observed in Temple syndrome, including speech delay. CONCLUSIONS: These data provide experimental evidence that, in humans, triplication can lead to segmental UPD and imprinting disease. Importantly, genotype/phenotype analyses further reveal how a post-zygotically generated complex structural variant, resulting from a replication-based mutational mechanism, contributes to expanding the clinical phenotype of known genetic syndromes. Mechanistically, such events can distort transmission genetics resulting in homozygosity at a locus for which only one parent is a carrier as well as cause imprinting diseases.

Lack of GAS2L2 Causes PCD by Impairing Cilia Orientation and Mucociliary Clearance. - Bustamante-Marin, Ximena M; Yin, Wei-Ning; Sears, Patrick R; Werner, Michael E; Brotslaw, Eva J; Mitchell, Brian J; Jania, Corey M; Zeman, Kirby L; Rogers, Troy D; Herring, Laura E; Refabért, Luc; Thomas, Lucie; et al. (Am J Hum Genet, 2019)
Primary ciliary dyskinesia (PCD) is a genetic disorder in which impaired ciliary function leads to chronic airway disease. Exome sequencing of a PCD subject identified an apparent homozygous frameshift variant, c.887_890delTAAG (p.Val296Glyfs13), in exon 5; this frameshift introduces a stop codon in amino acid 308 of the growth arrest-specific protein 2-like 2 (GAS2L2). Further genetic screening of unrelated PCD subjects identified a second proband with a compound heterozygous variant carrying the identical frameshift variant and a large deletion (c.867_343+1207del; p.?) starting in exon 5. Both individuals had clinical features of PCD but normal ciliary axoneme structure. In this research, using human nasal cells, mouse models, and X.laevis embryos, we show that GAS2L2 is abundant at the apical surface of ciliated cells, where it localizes with basal bodies, basal feet, rootlets, and actin filaments. Cultured GAS2L2-deficient nasal epithelial cells from one of the affected individuals showed defects in ciliary orientation and had an asynchronous and hyperkinetic (GAS2L2-deficient = 19.8 Hz versus control = 15.8 Hz) ciliary-beat pattern. These results were recapitulated in Gas2l2 mouse tracheal epithelial cell (mTEC) cultures and in X. laevis embryos treated with Gas2l2 morpholinos. In mice, the absence of Gas2l2 caused neonatal death, and the conditional deletion of Gas2l2 impaired mucociliary clearance (MCC) and led to mucus accumulation. These results show that a pathogenic variant in GAS2L2 causes a genetic defect in ciliary orientation and impairs MCC and results in PCD.
Keywords: Animals; Cilia; Ciliary Motility Disorders; Disease Models, Animal; Exons; Female; Gene Deletion; Genes, Lethal; Humans; Male; Mice; Mice, Knockout; Microfilament Proteins; Microtubule-Associated Proteins; Phenotype; Rotation; Xenopus

Loss of function, missense, and intronic variants in NOTCH1 confer different risks for left ventricular outflow tract obstructive heart defects in two European cohorts. - Helle, Emmi; Córdova-Palomera, Aldo; Ojala, Tiina; Saha, Priyanka; Potiny, Praneetha; Gustafsson, Stefan; Ingelsson, Erik; Bamshad, Michael; Nickerson, Deborah; Chong, Jessica X; Ashley, Euan; Priest, James R (Genet Epidemiol, 2019)
Loss of function variants in NOTCH1 cause left ventricular outflow tract obstructive defects (LVOTO). However, the risk conferred by rare and noncoding variants in NOTCH1 for LVOTO remains largely uncharacterized. In a cohort of 49 families affected by hypoplastic left heart syndrome, a severe form of LVOTO, we discovered predicted loss of function NOTCH1 variants in 6% of individuals. Rare or low-frequency missense variants were found in 16% of families. To make a quantitative estimate of the genetic risk posed by variants in NOTCH1 for LVOTO, we studied associations of 400 coding and noncoding variants in NOTCH1 in 1,085 cases and 332,788 controls from the UK Biobank. Two rare intronic variants in strong linkage disequilibrium displayed significant association with risk for LVOTO amongst European-ancestry individuals. This result was replicated in an independent analysis of 210 cases and 68,762 controls of non-European and mixed ancestry. In conclusion, carrying rare predicted loss of function variants in NOTCH1 confer significant risk for LVOTO. In addition, the two intronic variants seem to be associated with an increased risk for these defects. Our approach demonstrates the utility of population-based data sets in quantifying the specific risk of individual variants for disease-related phenotypes.
Keywords: Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Introns; Loss of Function Mutation; Male; Mutation, Missense; Pedigree; Receptor, Notch1; Risk Factors; Ventricular Outflow Obstruction; Whole Exome Sequencing

Loss of SMPD4 Causes a Developmental Disorder Characterized by Microcephaly and Congenital Arthrogryposis. - Magini, Pamela; Smits, Daphne J; Vandervore, Laura; Schot, Rachel; Columbaro, Marta; Kasteleijn, Esmee; van der Ent, Mees; Palombo, Flavia; Lequin, Maarten H; Dremmen, Marjolein; de Wit, Marie Claire Y; Severino, Mariasavina; et al. (Am J Hum Genet, 2019)
Sphingomyelinases generate ceramide from sphingomyelin as a second messenger in intracellular signaling pathways involved in cell proliferation, differentiation, or apoptosis. Children from 12 unrelated families presented with microcephaly, simplified gyral pattern of the cortex, hypomyelination, cerebellar hypoplasia, congenital arthrogryposis, and early fetal/postnatal demise. Genomic analysis revealed bi-allelic loss-of-function variants in SMPD4, coding for the neutral sphingomyelinase-3 (nSMase-3/SMPD4). Overexpression of human Myc-tagged SMPD4 showed localization both to the outer nuclear envelope and the ER and additionally revealed interactions with several nuclear pore complex proteins by proteomics analysis. Fibroblasts from affected individuals showed ER cisternae abnormalities, suspected for increased autophagy, and were more susceptible to apoptosis under stress conditions, while treatment with siSMPD4 caused delayed cell cycle progression. Our data show that SMPD4 links homeostasis of membrane sphingolipids to cell fate by regulating the cross-talk between the ER and the outer nuclear envelope, while its loss reveals a pathogenic mechanism in microcephaly.

Loss of the sphingolipid desaturase DEGS1 causes hypomyelinating leukodystrophy. - Pant, Devesh C; Dorboz, Imen; Schluter, Agatha; Fourcade, Stéphane; Launay, Nathalie; Joya, Javier; Aguilera-Albesa, Sergio; Yoldi, Maria Eugenia; Casasnovas, Carlos; Willis, Mary J; Ruiz, Montserrat; Ville, Dorothée; et al. (J Clin Invest, 2019)
Sphingolipid imbalance is the culprit in a variety of neurological diseases, some affecting the myelin sheath. We have used whole-exome sequencing in patients with undetermined leukoencephalopathies to uncover the endoplasmic reticulum lipid desaturase DEGS1 as the causative gene in 19 patients from 13 unrelated families. Shared features among the cases include severe motor arrest, early nystagmus, dystonia, spasticity, and profound failure to thrive. MRI showed hypomyelination, thinning of the corpus callosum, and progressive thalamic and cerebellar atrophy, suggesting a critical role of DEGS1 in myelin development and maintenance. This enzyme converts dihydroceramide (DhCer) into ceramide (Cer) in the final step of the de novo biosynthesis pathway. We detected a marked increase of the substrate DhCer and DhCer/Cer ratios in patients' fibroblasts and muscle. Further, we used a knockdown approach for disease modeling in Danio rerio, followed by a preclinical test with the first-line treatment for multiple sclerosis, fingolimod (FTY720, Gilenya). The enzymatic inhibition of Cer synthase by fingolimod, 1 step prior to DEGS1 in the pathway, reduced the critical DhCer/Cer imbalance and the severe locomotor disability, increasing the number of myelinating oligodendrocytes in a zebrafish model. These proof-of-concept results pave the way to clinical translation.

MAGEL2-related disorders: A study and case series. - Patak, Jameson; Gilfert, James; Byler, Melissa; Neerukonda, Vamsee; Thiffault, Isabelle; Cross, Laura; Amudhavalli, Shivarajan; Pacio-Miguez, Marta; Palomares-Bralo, Maria; Garcia-Minaur, Sixto; Santos-Simarro, Fernando; Powis, Zöe; et al. (Clin Genet, 2019)
Pathogenic MAGEL2 variants result in the phenotypes of Chitayat-Hall syndrome (CHS), Schaaf-Yang syndrome (SYS) and Prader-Willi syndrome (PWS). We present five patients with mutations in MAGEL2, including the first patient reported with a missense variant, adding to the limited literature. Further, we performed a systematic review of the CHS and SYS literature, assess the overlap between CHS, SYS and PWS, and analyze genotype-phenotype correlations among them. We conclude that there is neither a clinical nor etiological difference between CHS and SYS, and propose that the two syndromes simply be referred to as MAGEL2-related disorders.

Megabase Length Hypermutation Accompanies Human Structural Variation at 17p11.2. - Beck, Christine R; Carvalho, Claudia M B; Akdemir, Zeynep C; Sedlazeck, Fritz J; Song, Xiaofei; Meng, Qingchang; Hu, Jianhong; Doddapaneni, Harsha; Chong, Zechen; Chen, Edward S; Thornton, Philip C; Liu, Pengfei; et al. (Cell, 2019)
DNA rearrangements resulting in human genome structural variants (SVs) are caused by diverse mutational mechanisms. We used long- and short-read sequencing technologies to investigate end products of de novo chromosome 17p11.2 rearrangements and query the molecular mechanisms underlying both recurrent and non-recurrent events. Evidence for an increased rate of clustered single-nucleotide variant (SNV) mutation in cis with non-recurrent rearrangements was found. Indel and SNV formation are associated with both copy-number gains and losses of 17p11.2, occur up to ∼1 Mb away from the breakpoint junctions, and favor C > G transversion substitutions; results suggest that single-stranded DNA is formed during the genesis of the SV and provide compelling support for a microhomology-mediated break-induced replication (MMBIR) mechanism for SV formation. Our data show an additional mutational burden of MMBIR consisting of hypermutation confined to the locus and manifesting as SNVs and indels predominantly within genes.

Mendelian Gene Discovery: Fast and Furious with No End in Sight. - Bamshad, Michael J; Nickerson, Deborah A; Chong, Jessica X (Am J Hum Genet, 2019)
Gene discovery for Mendelian conditions (MCs) offers a direct path to understanding genome function. Approaches based on next-generation sequencing applied at scale have dramatically accelerated gene discovery and transformed genetic medicine. Finding the genetic basis of ∼6,000-13,000 MCs yet to be delineated will require both technical and computational innovation, but will rely to a larger extent on meaningful data sharing.

MendelProb: probability and sample size calculations for Mendelian studies of exome and whole genome sequence data. - He, Zongxiao; Wang, Lu; DeWan, Andrew T; Leal, Suzanne M (Bioinformatics, 2019)
Motivation: For the design of genetic studies, it is necessary to perform power calculations. Although for Mendelian traits the power of detecting linkage for pedigree(s) can be determined, it is also of great interest to determine the probability of identifying multiple pedigrees or unrelated cases with variants in the same gene. For many diseases, due to extreme locus heterogeneity this probability can be small. If only one family is observed segregating a variant classified as likely pathogenic or of unknown significance, the gene cannot be implicated in disease etiology. The probability of identifying several disease families or cases is dependent on the gene-specific disease prevalence and the sample size. The observation of multiple disease families or cases with variants in the same gene as well as evidence of pathogenicity from other sources, e.g. in silico prediction, expression and functional studies, can aid in implicating a gene in disease etiology. MendelProb can determine the probability of detecting a minimum number of families or cases with variants in the same gene. It can also calculate the probability of detecting genes with variants in different data types, e.g. identifying a variant in at least one family that can establish linkage and more the two additional families regardless of their size. Additionally, for a specified probability MendelProb can determine the number of probands which need to be screened to detect a minimum number of individuals with variants within the same gene. Results: A single Mendelian disease family is not sufficient to implicate a gene in disease etiology. It is necessary to observe multiple families or cases with potentially pathogenic variants in the same gene. MendelProb, an R library, was developed to determine the probability of observing multiple families and cases with variants within a gene and to also establish the numbers of probands to screen to detect multiple observations of variants within a gene. Availability and implementation: https://github.com/statgenetics/mendelprob.
Keywords: Exome; Genetic Linkage; Genomics; Humans; Pedigree; Probability; Sample Size; Software

metaFARVAT: An Efficient Tool for Meta-Analysis of Family-Based, Case-Control, and Population-Based Rare Variant Association Studies. - Wang, Longfei; Lee, Sungyoung; Qiao, Dandi; Cho, Michael H; Silverman, Edwin K; Lange, Christoph; Won, Sungho (Front Genet, 2019)
Family-based designs have been shown to be powerful in detecting the significant rare variants associated with human diseases. However, very few significant results have been found owing to relatively small sample sizes and the fact that statistical analyses often suffer from high false-negative error rates. These limitations can be avoided by combining results from multiple studies via meta-analysis. However, statistical methods for meta-analysis with rare variants are limited for family-based samples. In this report, we propose a tool for the meta-analysis of family-based rare variant associations, metaFARVAT. metaFARVAT is based on a quasi-likelihood score for each variant. These scores are combined to generate burden test, variable-threshold test, sequence kernel association test (SKAT), and optimal SKAT statistics. The proposed method tests homogeneous and heterogeneous effects of variants among different studies and can be applied to both quantitative and dichotomous phenotypes. Simulation results demonstrated the robustness and efficiency of the proposed method in different scenarios. By applying metaFARVAT to data from a family-based study and a case-control study, we identified a few promising candidate genes, including , which is associated with chronic obstructive pulmonary disease.

Missense Variants in the Histone Acetyltransferase Complex Component Gene TRRAP Cause Autism and Syndromic Intellectual Disability. - Cogné, Benjamin; Ehresmann, Sophie; Beauregard-Lacroix, Eliane; Rousseau, Justine; Besnard, Thomas; Garcia, Thomas; Petrovski, Slavé; Avni, Shiri; McWalter, Kirsty; Blackburn, Patrick R; Sanders, Stephan J; Uguen, Kévin; et al. (Am J Hum Genet, 2019)
Acetylation of the lysine residues in histones and other DNA-binding proteins plays a major role in regulation of eukaryotic gene expression. This process is controlled by histone acetyltransferases (HATs/KATs) found in multiprotein complexes that are recruited to chromatin by the scaffolding subunit transformation/transcription domain-associated protein (TRRAP). TRRAP is evolutionarily conserved and is among the top five genes intolerant to missense variation. Through an international collaboration, 17 distinct de novo or apparently de novo variants were identified in TRRAP in 24 individuals. A strong genotype-phenotype correlation was observed with two distinct clinical spectra. The first is a complex, multi-systemic syndrome associated with various malformations of the brain, heart, kidneys, and genitourinary system and characterized by a wide range of intellectual functioning; a number of affected individuals have intellectual disability (ID) and markedly impaired basic life functions. Individuals with this phenotype had missense variants clustering around the c.3127G>A p.(Ala1043Thr) variant identified in five individuals. The second spectrum manifested with autism spectrum disorder (ASD) and/or ID and epilepsy. Facial dysmorphism was seen in both groups and included upslanted palpebral fissures, epicanthus, telecanthus, a wide nasal bridge and ridge, a broad and smooth philtrum, and a thin upper lip. RNA sequencing analysis of skin fibroblasts derived from affected individuals skin fibroblasts showed significant changes in the expression of several genes implicated in neuronal function and ion transport. Thus, we describe here the clinical spectrum associated with TRRAP pathogenic missense variants, and we suggest a genotype-phenotype correlation useful for clinical evaluation of the pathogenicity of the variants.

Monogenic causes of chronic kidney disease in adults. - Connaughton, Dervla M; Kennedy, Claire; Shril, Shirlee; Mann, Nina; Murray, Susan L; Williams, Patrick A; Conlon, Eoin; Nakayama, Makiko; van der Ven, Amelie T; Ityel, Hadas; Kause, Franziska; Kolvenbach, Caroline M; et al. (Kidney Int, 2019)
Approximately 500 monogenic causes of chronic kidney disease (CKD) have been identified, mainly in pediatric populations. The frequency of monogenic causes among adults with CKD has been less extensively studied. To determine the likelihood of detecting monogenic causes of CKD in adults presenting to nephrology services in Ireland, we conducted whole exome sequencing (WES) in a multi-centre cohort of 114 families including 138 affected individuals with CKD. Affected adults were recruited from 78 families with a positive family history, 16 families with extra-renal features, and 20 families with neither a family history nor extra-renal features. We detected a pathogenic mutation in a known CKD gene in 42 of 114 families (37%). A monogenic cause was identified in 36% of affected families with a positive family history of CKD, 69% of those with extra-renal features, and only 15% of those without a family history or extra-renal features. There was no difference in the rate of genetic diagnosis in individuals with childhood versus adult onset CKD. Among the 42 families in whom a monogenic cause was identified, WES confirmed the clinical diagnosis in 17 (40%), corrected the clinical diagnosis in 9 (22%), and established a diagnosis for the first time in 16 families referred with CKD of unknown etiology (38%). In this multi-centre study of adults with CKD, a molecular genetic diagnosis was established in over one-third of families. In the evolving era of precision medicine, WES may be an important tool to identify the cause of CKD in adults.

MSTO1 mutations cause mtDNA depletion, manifesting as muscular dystrophy with cerebellar involvement. - Donkervoort, S; Sabouny, R; Yun, P; Gauquelin, L; Chao, K R; Hu, Y; Al Khatib, I; Töpf, A; Mohassel, P; Cummings, B B; Kaur, R; Saade, D; et al. (Acta Neuropathol, 2019)
MSTO1 encodes a cytosolic mitochondrial fusion protein, misato homolog 1 or MSTO1. While the full genotype-phenotype spectrum remains to be explored, pathogenic variants in MSTO1 have recently been reported in a small number of patients presenting with a phenotype of cerebellar ataxia, congenital muscle involvement with histologic findings ranging from myopathic to dystrophic and pigmentary retinopathy. The proposed underlying pathogenic mechanism of MSTO1-related disease is suggestive of impaired mitochondrial fusion secondary to a loss of function of MSTO1. Disorders of mitochondrial fusion and fission have been shown to also lead to mitochondrial DNA (mtDNA) depletion, linking them to the mtDNA depletion syndromes, a clinically and genetically diverse class of mitochondrial diseases characterized by a reduction of cellular mtDNA content. However, the consequences of pathogenic variants in MSTO1 on mtDNA maintenance remain poorly understood. We present extensive phenotypic and genetic data from 12 independent families, including 15 new patients harbouring a broad array of bi-allelic MSTO1 pathogenic variants, and we provide functional characterization from seven MSTO1-related disease patient fibroblasts. Bi-allelic loss-of-function variants in MSTO1 manifest clinically with a remarkably consistent phenotype of childhood-onset muscular dystrophy, corticospinal tract dysfunction and early-onset non-progressive cerebellar atrophy. MSTO1 protein was not detectable in the cultured fibroblasts of all seven patients evaluated, suggesting that pathogenic variants result in a loss of protein expression and/or affect protein stability. Consistent with impaired mitochondrial fusion, mitochondrial networks in fibroblasts were found to be fragmented. Furthermore, all fibroblasts were found to have depletion of mtDNA ranging from 30 to 70% along with alterations to mtDNA nucleoids. Our data corroborate the role of MSTO1 as a mitochondrial fusion protein and highlight a previously unrecognized link to mtDNA regulation. As impaired mitochondrial fusion is a recognized cause of mtDNA depletion syndromes, this novel link to mtDNA depletion in patient fibroblasts suggests that MSTO1-deficiency should also be considered a mtDNA depletion syndrome. Thus, we provide mechanistic insight into the disease pathogenesis associated with MSTO1 mutations and further define the clinical spectrum and the natural history of MSTO1-related disease.

Mutations in and previously unimplicated genes of the BMP, Wnt, and Hedgehog pathways in syndromic craniosynostosis. - Timberlake, Andrew T; Jin, Sheng Chih; Nelson-Williams, Carol; Wu, Robin; Furey, Charuta G; Islam, Barira; Haider, Shozeb; Loring, Erin; Galm, Amy; Steinbacher, Derek M; Larysz, Dawid; Staffenberg, David A; et al. (Proc Natl Acad Sci U S A, 2019)
Craniosynostosis (CS) is a frequent congenital anomaly featuring the premature fusion of 1 or more sutures of the cranial vault. Syndromic cases, featuring additional congenital anomalies, make up 15% of CS. While many genes underlying syndromic CS have been identified, the cause of many syndromic cases remains unknown. We performed exome sequencing of 12 syndromic CS cases and their parents, in whom previous genetic evaluations were unrevealing. Damaging de novo or transmitted loss of function (LOF) mutations were found in 8 genes that are highly intolerant to LOF mutation ( = 4.0 × 10); additionally, a rare damaging mutation in , which has a lower level of intolerance, was identified. Four probands had rare damaging mutations (2 de novo) in , a transcription factor that orchestrates neural crest cell migration and differentiation; this mutation burden is highly significant ( = 8.2 × 10). Three probands had rare damaging mutations in , , or , which function in the Hedgehog, BMP, and Wnt signaling pathways; other genes in these pathways have previously been implicated in syndromic CS. Similarly, damaging de novo mutations were identified in genes encoding the chromatin modifier , and , encoding catenin α-1. These findings establish as a CS gene, have implications for assessing risk to subsequent children in these families, and provide evidence implicating other genes in syndromic CS. This high yield indicates the value of performing exome sequencing of syndromic CS patients when sequencing of known disease loci is unrevealing.

Mutations in ANKLE2, a ZIKA Virus Target, Disrupt an Asymmetric Cell Division Pathway in Drosophila Neuroblasts to Cause Microcephaly. - Link, Nichole; Chung, Hyunglok; Jolly, Angad; Withers, Marjorie; Tepe, Burak; Arenkiel, Benjamin R; Shah, Priya S; Krogan, Nevan J; Aydin, Hatip; Geckinli, Bilgen B; Tos, Tulay; Isikay, Sedat; et al. (Dev Cell, 2019)
The apical Par complex, which contains atypical protein kinase C (aPKC), Bazooka (Par-3), and Par-6, is required for establishing polarity during asymmetric division of neuroblasts in Drosophila, and its activity depends on L(2)gl. We show that loss of Ankle2, a protein associated with microcephaly in humans and known to interact with Zika protein NS4A, reduces brain volume in flies and impacts the function of the Par complex. Reducing Ankle2 levels disrupts endoplasmic reticulum (ER) and nuclear envelope morphology, releasing the kinase Ballchen-VRK1 into the cytosol. These defects are associated with reduced phosphorylation of aPKC, disruption of Par-complex localization, and spindle alignment defects. Importantly, removal of one copy of ballchen or l(2)gl suppresses Ankle2 mutant phenotypes and restores viability and brain size. Human mutational studies implicate the above-mentioned genes in microcephaly and motor neuron disease. We suggest that NS4A, ANKLE2, VRK1, and LLGL1 define a pathway impinging on asymmetric determinants of neural stem cell division.

Mutations in GDF11 and the extracellular antagonist, Follistatin, as a likely cause of Mendelian forms of orofacial clefting in humans. - Cox, Timothy C; Lidral, Andrew C; McCoy, Jason C; Liu, Huan; Cox, Liza L; Zhu, Ying; Anderson, Ryan D; Moreno Uribe, Lina M; Anand, Deepti; Deng, Mei; Richter, Chika T; Nidey, Nichole L; et al. (Hum Mutat, 2019)
Cleft lip with or without cleft palate (CL/P) is generally viewed as a complex trait with multiple genetic and environmental contributions. In 70% of cases, CL/P presents as an isolated feature and/or deemed nonsyndromic. In the remaining 30%, CL/P is associated with multisystem phenotypes or clinically recognizable syndromes, many with a monogenic basis. Here we report the identification, via exome sequencing, of likely pathogenic variants in two genes that encode interacting proteins previously only linked to orofacial clefting in mouse models. A variant in GDF11 (encoding growth differentiation factor 11), predicting a p.(Arg298Gln) substitution at the Furin protease cleavage site, was identified in one family that segregated with CL/P and both rib and vertebral hypersegmentation, mirroring that seen in Gdf11 knockout mice. In the second family in which CL/P was the only phenotype, a mutation in FST (encoding the GDF11 antagonist, Follistatin) was identified that is predicted to result in a p.(Cys56Tyr) substitution in the region that binds GDF11. Functional assays demonstrated a significant impact of the specific mutated amino acids on FST and GDF11 function and, together with embryonic expression data, provide strong evidence for the importance of GDF11 and Follistatin in the regulation of human orofacial development.

Mutations in KIRREL1, a slit diaphragm component, cause steroid-resistant nephrotic syndrome. - Solanki, Ashish K; Widmeier, Eugen; Arif, Ehtesham; Sharma, Shailza; Daga, Ankana; Srivastava, Pankaj; Kwon, Sang-Ho; Hugo, Hannah; Nakayama, Makiko; Mann, Nina; Majmundar, Amar J; Tan, Wei; et al. (Kidney Int, 2019)
Steroid-resistant nephrotic syndrome is a frequent cause of chronic kidney disease almost inevitably progressing to end-stage renal disease. More than 58 monogenic causes of SRNS have been discovered and majority of known steroid-resistant nephrotic syndrome causing genes are predominantly expressed in glomerular podocytes, placing them at the center of disease pathogenesis. Herein, we describe two unrelated families with steroid-resistant nephrotic syndrome with homozygous mutations in the KIRREL1 gene. One mutation showed high frequency in the European population (minor allele frequency 0.0011) and this patient achieved complete remission following treatment, but later progressed to chronic kidney disease. We found that mutant KIRREL1 proteins failed to localize to the podocyte cell membrane, indicating defective trafficking and impaired podocytes function. Thus, the KIRREL1 gene product has an important role in modulating the integrity of the slit diaphragm and maintaining glomerular filtration function.

Mutations in PERP Cause Dominant and Recessive Keratoderma. - Duchatelet, Sabine; Boyden, Lynn M; Ishida-Yamamoto, Akemi; Zhou, Jing; Guibbal, Laure; Hu, Ronghua; Lim, Young H; Bole-Feysot, Christine; Nitschké, Patrick; Santos-Simarro, Fernando; de Lucas, Raul; Milstone, Leonard M; et al. (J Invest Dermatol, 2019)
Investigation of genetic determinants of Mendelian skin disorders has substantially advanced understanding of epidermal biology. Here we show that mutations in PERP, encoding a crucial component of desmosomes, cause both dominant and recessive human keratoderma. Heterozygosity for a C-terminal truncation, which produces a protein that appears to be unstably incorporated into desmosomes, causes Olmsted syndrome with severe periorificial and palmoplantar keratoderma in multiple unrelated kindreds. Homozygosity for an N-terminal truncation ablates expression and causes widespread erythrokeratoderma, with expansion of epidermal differentiation markers. Both exhibit epidermal hyperproliferation, immature desmosomes lacking a dense midline observed via electron microscopy, and impaired intercellular adhesion upon mechanical stress. Localization of other desmosomal components appears normal, which is in contrast to other conditions caused by mutations in genes encoding desmosomal proteins. These discoveries highlight the essential role of PERP in human desmosomes and epidermal homeostasis and further expand the heterogeneous spectrum of inherited keratinization disorders.

Nasal Nitric Oxide in Primary Immunodeficiency and Primary Ciliary Dyskinesia: Helping to Distinguish Between Clinically Similar Diseases. - Zysman-Colman, Zofia N; Kaspy, Kimberley R; Alizadehfar, Reza; Nykamp, Keith R; Zariwala, Maimoona A; Knowles, Michael R; Vinh, Donald C; Shapiro, Adam J (J Clin Immunol, 2019)
PURPOSE: Primary ciliary dyskinesia (PCD) is a rare disorder of the mucociliary clearance leading to recurrent upper and lower respiratory tract infections. PCD is difficult to clinically distinguish from other entities leading to recurrent oto-sino-pulmonary infections, including primary immunodeficiency (PID). Nasal nitric oxide (nNO) is a sensitive and specific diagnostic test for PCD, but it has not been thoroughly examined in PID. Past publications have suggested an overlap in nNO levels among subjects with PCD and PID. We sought to determine if nNO measurements among patients diagnosed with PID would fall significantly above the established PCD diagnostic cutoff value of 77 nL/min. METHODS: Children > 5 years old and adults with definitive PID or PCD diagnoses were recruited from outpatient subspecialty clinics. Participants underwent nNO testing by standardized protocol using a chemiluminescence analyzer and completed a questionnaire concerning their chronic oto-sino-pulmonary symptoms, including key clinical criteria specific to diagnosed PCD (neonatal respiratory distress at term birth, year-round cough or nasal congestion starting before 6 months of age, any organ laterality defect). RESULTS: Participants included 32 patients with PID, 27 patients with PCD, and 19 healthy controls. Median nNO was 228.9.1 nL/min in the PID group, 19.7 nL/min in the PCD group, and 269.4 in the healthy controls (p < 0.0001). Subjects with PCD were significantly more likely to report key clinical criteria specific to PCD, but approximately 25% of PID subjects also reported at least 1 of these key clinical criteria (mainly year-round cough or nasal congestion). CONCLUSIONS: While key clinical criteria associated with PCD often overlap with the symptoms reported in PID, nNO measurement by chemiluminescence technology allows for effective discrimination between PID and PCD.

A new NBIA patient from Turkey with homozygous C19ORF12 mutation. - Kasapkara, Çiğdem Seher; Tümer, Leyla; Gregory, Allison; Ezgü, Fatih; İnci, Aslı; Derinkuyu, Betül Emine; Fox, Rachel; Rogers, Caleb; Hayflick, Susan (Acta Neurol Belg, 2019)

A novel case of Greenberg dysplasia and genotype-phenotype correlation analysis for LBR pathogenic variants: An instructive example of one gene-multiple phenotypes. - Giorgio, Elisa; Sirchia, Fabio; Bosco, Martino; Sobreira, Nara Lygia M; Grosso, Enrico; Brussino, Alessandro; Brusco, Alfredo (Am J Med Genet A, 2019)
Greenberg skeletal dysplasia is an autosomal recessive, perinatal lethal disorder associated with biallelic variants affecting the lamin B receptor (LBR) gene. LBR is also associated with the autosomal recessive anadysplasia-like spondylometaphyseal dysplasia, and the autosomal dominant Pelger-Huët anomaly, a benign laminopathy characterized by anomalies in the nuclear shape of blood granulocytes. The LBR is an inner nuclear membrane protein that binds lamin B proteins (LMNB1 and LMNB2), interacts with chromatin, and exerts a sterol reductase activity. Here, we report on a novel LBR missense variant [c.1379A>G; p.(D460R)], identified by whole exome sequencing and causing Greenberg dysplasia in two fetuses from a consanguineous Moroccan family. We revised published LBR variants to propose a genotype-phenotype correlation in LBR associated diseases. The diverse phenotypes are correlated to the functional domain affected, the heterozygous or homozygous state of the variants, and their different impact on the residual protein function. LBR represents an instructive example of one gene presenting with two different patterns of inheritance and at least three different clinical phenotypes.

Novel Heterozygous Mutation in Is Associated With Early Onset CVID and a Functional Defect in NK Cells Complicated by Disseminated CMV Infection and Severe Nephrotic Syndrome. - Aird, Alejandra; Lagos, Macarena; Vargas-Hernandez, Alexander; Posey, Jennifer E; Coban-Akdemir, Zeynep; Jhangiani, Shalini; Mace, Emily M; Reyes, Anaid; King, Alejandra; Cavagnaro, Felipe; Forbes, Lisa R; Chinn, Ivan K; et al. (Front Pediatr, 2019)
Nuclear factor kappa-B subunit 2 (NF-κB2/p100/p52), encoded by (MIM: 164012) belongs to the NF-κB family of transcription factors that play a critical role in inflammation, immunity, cell proliferation, differentiation and survival. Heterozygous C-terminal mutations in have been associated with early-onset common variable immunodeficiency (CVID), central adrenal insufficiency and ectodermal dysplasia. Only two previously reported cases have documented decreased natural killer (NK) cell cytotoxicity, and little is known about the role of NF-κB2 in NK cell maturation and function. Here we report a 13-year-old female that presented at 6 years of age with a history of early onset recurrent sinopulmonary infections, progressive hair loss, and hypogamaglobulinemia consistent with a clinical diagnosis of CVID. At 9 years of age she had cytomegalovirus (CMV) pneumonia that responded to ganciclovir treatment. Functional NK cell testing demonstrated decreased NK cell cytotoxicity despite normal NK cell numbers, consistent with a greater susceptibility to systemic CMV infection. Research exome sequencing (ES) was performed and revealed a novel heterozygous nonsense mutation in (c.2611C>T, p.Gln871) that was not carried by either of her parents. The variant was Sanger sequenced and confirmed to be in the patient. At age 12, she presented with a reactivation of the systemic CMV infection that was associated with severe and progressive nephrotic syndrome with histologic evidence of pedicellar effacement and negative immunofluorescence. To our knowledge, this is the third NF-κB2 deficient patient in which an abnormal NK cell function has been observed, suggesting a role for non-canonical NF-κB2 signaling in NK cell cytotoxicity. NK cell function should be assessed in patients with mutations in the non-canonical NF-κB pathway to explore the risk for systemic viral infections that may lead to severe complications and impact patient survival. Similarly NF-κB2 should be considered in patients with combined immunodeficiency who have aberrant NK cell function. Further studies are needed to characterize the role of NF-κB2 in NK cell cytotoxic function.

Novel homozygous ENPP1 mutation causes generalized arterial calcifications of infancy, thrombocytopenia, and cardiovascular and central nervous system syndrome. - Staretz-Chacham, Orna; Shukrun, Rachel; Barel, Ortal; Pode-Shakked, Ben; Pleniceanu, Oren; Anikster, Yair; Shalva, Nechama; Ferreira, Carlos R; Ben-Haim Kadosh, Admit; Richardson, Justin; Mane, Shrikant M; Hildebrandt, Friedhelm; et al. (Am J Med Genet A, 2019)
Generalized arterial calcifications of infancy (GACI) is caused by mutations in ENPP1. Other ENPP1-related phenotypes include pseudoxanthoma elasticum, hypophosphatemic rickets, and Cole disease. We studied four children from two Bedouin consanguineous families who presented with severe clinical phenotype including thrombocytopenia, hypoglycemia, hepatic, and neurologic manifestations. Initial working diagnosis included congenital infection; however, patients remained without a definitive diagnosis despite extensive workup. Consequently, we investigated a potential genetic etiology. Whole exome sequencing (WES) was performed for affected children and their parents. Following the identification of a novel mutation in the ENPP1 gene, we characterized this novel multisystemic presentation and revised relevant imaging studies. Using WES, we identified a novel homozygous mutation (c.556G > C; p.Gly186Arg) in ENPP1 which affects a highly conserved protein domain (somatomedin B2). ENPP1-associated genetic diseases exhibit phenotypic heterogeneity depending on mutation type and location. Follow-up clinical characterization of these families allowed us to revise and detect new features of systemic calcifications, which established the diagnosis of GACI, expanding the phenotypic spectrum associated with ENPP1 mutations. Our findings demonstrate that this novel ENPP1 founder mutation can cause a fatal multisystemic phenotype, mimicking severe congenital infection. This also represents the first reported mutation affecting the SMB2 domain, associated with GACI.

Novel parent-of-origin-specific differentially methylated loci on chromosome 16. - Schulze, Katharina V; Szafranski, Przemyslaw; Lesmana, Harry; Hopkin, Robert J; Hamvas, Aaron; Wambach, Jennifer A; Shinawi, Marwan; Zapata, Gladys; Carvalho, Claudia M B; Liu, Qian; Karolak, Justyna A; Lupski, James R; et al. (Clin Epigenetics, 2019)
BACKGROUND: Congenital malformations associated with maternal uniparental disomy of chromosome 16, upd(16)mat, resemble those observed in newborns with the lethal developmental lung disease, alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV). Interestingly, ACDMPV-causative deletions, involving FOXF1 or its lung-specific upstream enhancer at 16q24.1, arise almost exclusively on the maternally inherited chromosome 16. Given the phenotypic similarities between upd(16)mat and ACDMPV, together with parental allelic bias in ACDMPV, we hypothesized that there may be unknown imprinted loci mapping to chromosome 16 that become functionally unmasked by chromosomal structural variants. RESULTS: To identify parent-of-origin biased DNA methylation, we performed high-resolution bisulfite sequencing of chromosome 16 on peripheral blood and cultured skin fibroblasts from individuals with maternal or paternal upd(16) as well as lung tissue from patients with ACDMPV-causative 16q24.1 deletions and a normal control. We identified 22 differentially methylated regions (DMRs) with ≥ 5 consecutive CpG methylation sites and varying tissue-specificity, including the known DMRs associated with the established imprinted gene ZNF597 and DMRs supporting maternal methylation of PRR25, thought to be paternally expressed in lymphoblastoid cells. Lastly, we found evidence of paternal methylation on 16q24.1 near LINC01082 mapping to the FOXF1 enhancer. CONCLUSIONS: Using high-resolution bisulfite sequencing to evaluate DNA methylation across chromosome 16, we found evidence for novel candidate imprinted loci on chromosome 16 that would not be evident in array-based assays and could contribute to the birth defects observed in patients with upd(16)mat or in ACDMPV.

Novel SPEG mutations in congenital myopathies: Genotype-phenotype correlations. - Qualls, Anita E; Donkervoort, Sandra; Herkert, Johanna C; D'Gama, Alissa M; Bharucha-Goebel, Diana; Collins, James; Chao, Katherine R; Foley, A Reghan; Schoots, Mirthe H; Jongbloed, Jan D H; Bönnemann, Carsten G; Agrawal, Pankaj B (Muscle Nerve, 2019)
INTRODUCTION: Centronuclear myopathies (CNMs) are a subtype of congenital myopathies (CMs) characterized by muscle weakness, predominant type 1 fibers, and increased central nuclei. SPEG (striated preferentially expressed protein kinase) mutations have recently been identified in 7 CM patients (6 with CNMs). We report 2 additional patients with SPEG mutations expanding the phenotype and evaluate genotype-phenotype correlations associated with SPEG mutations. METHODS: Using whole exome/genome sequencing in CM families, we identified novel recessive SPEG mutations in 2 patients. RESULTS: Patient 1, with severe muscle weakness requiring respiratory support, dilated cardiomyopathy, ophthalmoplegia, and findings of nonspecific CM on muscle biopsy carried a homozygous SPEG mutation (p.Val3062del). Patient 2, with milder muscle weakness, ophthalmoplegia, and CNM carried compound heterozygous mutations (p.Leu728Argfs*82) and (p.Val2997Glyfs*52). CONCLUSIONS: The 2 patients add insight into genotype-phenotype correlations of SPEG-associated CMs. Clinicians should consider evaluating a CM patient for SPEG mutations even in the absence of CNM features. Muscle Nerve 59:357-362, 2019.
Keywords: Biopsy; Child; Child, Preschool; Consanguinity; Exome; Female; Genetic Association Studies; Humans; Infant; Male; Muscle Proteins; Muscle Weakness; Muscle, Skeletal; Mutation; Myopathies, Structural, Congenital; Protein-Serine-Threonine Kinases; Sequence Analysis

Objective measures of sleep disturbances in children with Potocki-Lupski syndrome. - Kaplan, Kevin; McCool, Caroline; Lupski, James R; Glaze, Daniel; Potocki, Lorraine (Am J Med Genet A, 2019)
Potocki-Lupski syndrome (PTLS; MIM 610883) is a neurodevelopmental disorder caused by a microduplication, a 3.7 Mb copy number variant, mapping within chromosome 17p11.2, encompassing the dosage-sensitive RAI1 gene. Whereas RAI1 triplosensitivity causes PTLS, haploinsufficiency of RAI1 due to 17p11.2 microdeletion causes the clinically distinct Smith-Magenis syndrome (SMS; MIM 182290). Most individuals with SMS have an inversion of the melatonin cycle. Subjects with PTLS have mild sleep disturbances such as sleep apnea with no melatonin abnormalities described. Sleep patterns and potential disturbances in subjects with PTLS have not been objectively characterized. We delineated sleep characteristics in 23 subjects with PTLS who underwent a polysomnogram at Texas Children's Hospital. Eleven of these subjects (58%) completed the Child's Sleep Habits Questionnaire (CSHQ). Urinary melatonin was measured in one patient and published previously. While the circadian rhythm of melatonin in PTLS appears not to be disrupted, we identified significant differences in sleep efficiency, percentage of rapid eye movement sleep, oxygen nadir, obstructive apnea hypopnea index, and periodic limb movements between prepubertal subjects with PTLS and previously published normative data. Data from the CSHQ indicate that 64% (7/11) of parents do not identify a sleep disturbance in their children. Our data indicate that younger individuals, <10 years, with PTLS have statistically significant abnormalities in five components of sleep despite lack of recognition of substantial sleep disturbances by parents. Our data support the contention that patients with PTLS should undergo clinical evaluations for sleep disordered breathing and periodic limb movement disorder, both of which are treatable conditions.

Oral therapy for riboflavin transporter deficiency - What is the regimen of choice? - Gorcenco, Sorina; Vaz, Frédéric M; Tracewska-Siemiątkowska, Anna; Tranebjærg, Lisbeth; Cremers, Frans P M; Ygland, Emil; Kicsi, Jenő; Rendtorff, Nanna Dahl; Möller, Claes; Kjellström, Ulrika; Andréasson, Sten; Puschmann, Andreas (Parkinsonism Relat Disord, 2019)

Paralog Studies Augment Gene Discovery: DDX and DHX Genes. - Paine, Ingrid; Posey, Jennifer E; Grochowski, Christopher M; Jhangiani, Shalini N; Rosenheck, Sarah; Kleyner, Robert; Marmorale, Taylor; Yoon, Margaret; Wang, Kai; Robison, Reid; Cappuccio, Gerarda; Pinelli, Michele; et al. (Am J Hum Genet, 2019)
Members of a paralogous gene family in which variation in one gene is known to cause disease are eight times more likely to also be associated with human disease. Recent studies have elucidated DHX30 and DDX3X as genes for which pathogenic variant alleles are involved in neurodevelopmental disorders. We hypothesized that variants in paralogous genes encoding members of the DExD/H-box RNA helicase superfamily might also underlie developmental delay and/or intellectual disability (DD and/or ID) disease phenotypes. Here we describe 15 unrelated individuals who have DD and/or ID, central nervous system (CNS) dysfunction, vertebral anomalies, and dysmorphic features and were found to have probably damaging variants in DExD/H-box RNA helicase genes. In addition, these individuals exhibit a variety of other tissue and organ system involvement including ocular, outer ear, hearing, cardiac, and kidney tissues. Five individuals with homozygous (one), compound-heterozygous (two), or de novo (two) missense variants in DHX37 were identified by exome sequencing. We identified ten total individuals with missense variants in three other DDX/DHX paralogs: DHX16 (four individuals), DDX54 (three individuals), and DHX34 (three individuals). Most identified variants are rare, predicted to be damaging, and occur at conserved amino acid residues. Taken together, these 15 individuals implicate the DExD/H-box helicases in both dominantly and recessively inherited neurodevelopmental phenotypes and highlight the potential for more than one disease mechanism underlying these disorders.

Pathogenic Abnormal Splicing Due to Intronic Deletions that Induce Biophysical Space Constraint for Spliceosome Assembly. - Bryen, Samantha J; Joshi, Himanshu; Evesson, Frances J; Girard, Cyrille; Ghaoui, Roula; Waddell, Leigh B; Testa, Alison C; Cummings, Beryl; Arbuckle, Susan; Graf, Nicole; Webster, Richard; MacArthur, Daniel G; et al. (Am J Hum Genet, 2019)
A precise genetic diagnosis is the single most important step for families with genetic disorders to enable personalized and preventative medicine. In addition to genetic variants in coding regions (exons) that can change a protein sequence, abnormal pre-mRNA splicing can be devastating for the encoded protein, inducing a frameshift or in-frame deletion/insertion of multiple residues. Non-coding variants that disrupt splicing are extremely challenging to identify. Stemming from an initial clinical discovery in two index Australian families, we define 25 families with genetic disorders caused by a class of pathogenic non-coding splice variant due to intronic deletions. These pathogenic intronic deletions spare all consensus splice motifs, though they critically shorten the minimal distance between the 5' splice-site (5'SS) and branchpoint. The mechanistic basis for abnormal splicing is due to biophysical constraint precluding U1/U2 spliceosome assembly, which stalls in A-complexes (that bridge the 5'SS and branchpoint). Substitution of deleted nucleotides with non-specific sequences restores spliceosome assembly and normal splicing, arguing against loss of an intronic element as the primary causal basis. Incremental lengthening of 5'SS-branchpoint length in our index EMD case subject defines 45-47 nt as the critical elongation enabling (inefficient) spliceosome assembly for EMD intron 5. The 5'SS-branchpoint space constraint mechanism, not currently factored by genomic informatics pipelines, is relevant to diagnosis and precision medicine across the breadth of Mendelian disorders and cancer genomics.

Pathogenic Variants in GPC4 Cause Keipert Syndrome. - Amor, David J; Stephenson, Sarah E M; Mustapha, Mirna; Mensah, Martin A; Ockeloen, Charlotte W; Lee, Wei Shern; Tankard, Rick M; Phelan, Dean G; Shinawi, Marwan; de Brouwer, Arjan P M; Pfundt, Rolph; Dowling, Cari; et al. (Am J Hum Genet, 2019)
Glypicans are a family of cell-surface heparan sulfate proteoglycans that regulate growth-factor signaling during development and are thought to play a role in the regulation of morphogenesis. Whole-exome sequencing of the Australian family that defined Keipert syndrome (nasodigitoacoustic syndrome) identified a hemizygous truncating variant in the gene encoding glypican 4 (GPC4). This variant, located in the final exon of GPC4, results in premature termination of the protein 51 amino acid residues prior to the stop codon, and in concomitant loss of functionally important N-linked glycosylation (Asn514) and glycosylphosphatidylinositol (GPI) anchor (Ser529) sites. We subsequently identified seven affected males from five additional kindreds with novel and predicted pathogenic variants in GPC4. Segregation analysis and X-inactivation studies in carrier females provided supportive evidence that the GPC4 variants caused the condition. Furthermore, functional studies of recombinant protein suggested that the truncated proteins p.Gln506 and p.Glu496 were less stable than the wild type. Clinical features of Keipert syndrome included a prominent forehead, a flat midface, hypertelorism, a broad nose, downturned corners of mouth, and digital abnormalities, whereas cognitive impairment and deafness were variable features. Studies of Gpc4 knockout mice showed evidence of the two primary features of Keipert syndrome: craniofacial abnormalities and digital abnormalities. Phylogenetic analysis demonstrated that GPC4 is most closely related to GPC6, which is associated with a bone dysplasia that has a phenotypic overlap with Keipert syndrome. Overall, we have shown that pathogenic variants in GPC4 cause a loss of function that results in Keipert syndrome, making GPC4 the third human glypican to be linked to a genetic syndrome.

Pathogenic Variants in NUP214 Cause "Plugged" Nuclear Pore Channels and Acute Febrile Encephalopathy. - Fichtman, Boris; Harel, Tamar; Biran, Nitzan; Zagairy, Fadia; Applegate, Carolyn D; Salzberg, Yuval; Gilboa, Tal; Salah, Somaya; Shaag, Avraham; Simanovsky, Natalia; Ayoubieh, Houriya; Sobreira, Nara; et al. (Am J Hum Genet, 2019)
We report biallelic missense and frameshift pathogenic variants in the gene encoding human nucleoporin NUP214 causing acute febrile encephalopathy. Clinical symptoms include neurodevelopmental regression, seizures, myoclonic jerks, progressive microcephaly, and cerebellar atrophy. NUP214 and NUP88 protein levels were reduced in primary skin fibroblasts derived from affected individuals, while the total number and density of nuclear pore complexes remained normal. Nuclear transport assays exhibited defects in the classical protein import and mRNA export pathways in affected cells. Direct surface imaging of fibroblast nuclei by scanning electron microscopy revealed a large increase in the presence of central particles (known as "plugs") in the nuclear pore channels of affected cells. This observation suggests that large transport cargoes may be delayed in passage through the nuclear pore channel, affecting its selective barrier function. Exposure of fibroblasts from affected individuals to heat shock resulted in a marked delay in their stress response, followed by a surge in apoptotic cell death. This suggests a mechanistic link between decreased cell survival in cell culture and severe fever-induced brain damage in affected individuals. Our study provides evidence by direct imaging at the single nuclear pore level of functional changes linked to a human disease.

A Patient with Berardinelli-Seip Syndrome, Novel Splicesite Mutation and Concomitant Development of Non-diabetic Polyneuropathy - Oswiecimska, Joanna; Dawidziuk, Mateusz; Gambin, Tomasz; Ziora, Katarzyna; Marek, Marta; Rzonca, Sylwia; Guilbride, D. Lys; Jhangiani, Shalini N.; Obuchowicz, Anna; Sikora, Alicja; Lupski, James R.; Wiszniewski, Wojciech; et al. (J Clin Res Pediatr Endocrinol, 2019)
Primary polyneuropathy in the context of Seip-Berardinelli type 1 seipinopathy, or congenital generalized lipodystrophy type 1 (CGL1) has not been previously reported. We report the case history of a 27 year old female CGL1 patient presenting with an unusual additional development of non-diabetic peripheral neuropathy and learning disabilities in early adolescence. Whole exome sequencing (WES) of the patient genome identified a novel variant, homozygous for a 52 bp intronic deletion in the locus, coding for 1-acylglycerol-3-phosphate O-acyltransferase 2, which is uniquely associated with CGL1 seipinopathies, with no molecular evidence for dual diagnosis. Functional studies using RNA isolated from patient peripheral blood leucocytes showed abnormal RNA splicing resulting in the loss of 25 amino acids from the patient AGPAT2 protein coding sequence. Stability and transcription levels for the misspliced mRNA in our patient nonetheless remained normal. Any AGPAT2 protein produced in our patient is therefore likely to be dysfunctional. However, formal linkage of this deletion to the neuropathy observed remains to be shown. The classical clinical presentation of a patient with -associated lipodystrophy shows normal cognition and no development of polyneuropathy. Cognitive disabilities and polyneuropathy are features associated exclusively with clinical CGL type 2 arising from seipin gene mutations. This case study suggests that in some genetic contexts, mutations can also produce phenotypes with primary polyneuropathy.

Phenotypic expansion of POFUT1 loss of function mutations in a disorder featuring segmental dyspigmentation with eczematous and folliculo-centric lesions. - Atzmony, Lihi; Zaki, Theodore D; Antaya, Richard J; Choate, Keith A (Am J Med Genet A, 2019)
Appearance of mosaic disorders in thin Blaschko lines suggests that somatic mutations in keratinocyte precursors underlie their pathogenesis. Germline heterozygous mutations in POFUT1 gene cause Dowling-Degos disease (DDD), a skin disease that features flexural reticulated hyperpigmentation and follicular-based lesions. POFUT1 mosaicism has not been described to date. Here, we describe a 9-year-old female with segmental hyper- and hypopigmented patches with overlying eczematous plaques and follicular papules. Employing paired whole exome sequencing of saliva and keratinocytes isolated from affected skin, we found a novel germline heterozygous POFUT1 deletion causing frameshift and premature codon termination and somatic copy-neutral loss of heterozygosity on chromosome 20 encompassing POFUT1. Expression levels of POFUT1 as well as other key regulators of the notch signaling pathway-NOTCH1, NOTCH2, and HES1-were reduced in affected keratinocytes compared with normal keratinocytes. Our findings provide the first evidence of POFUT1 postzygotic mutation and a phenotypic expansion of POFUT1 loss of function mutations. We show that a recessive loss of function mutation in POFUT1 produces a distinct clinical presentation with features (e.g., dermatitis) that are absent in the generalized form of DDD. This study demonstrates how analysis of mosaic disorders can reveal unexpected phenotypes for known genes.

Primary Ciliary Dyskinesia: Longitudinal Study of Lung Disease by Ultrastructure Defect and Genotype. - Davis, Stephanie D; Rosenfeld, Margaret; Lee, Hye-Seung; Ferkol, Thomas W; Sagel, Scott D; Dell, Sharon D; Milla, Carlos; Pittman, Jessica E; Shapiro, Adam J; Sullivan, Kelli M; Nykamp, Keith R; Krischer, Jeffrey P; et al. (Am J Respir Crit Care Med, 2019)
RATIONALE: In primary ciliary dyskinesia, factors leading to disease heterogeneity are poorly understood. OBJECTIVES: To describe early lung disease progression in primary ciliary dyskinesia and identify associations between ultrastructural defects and genotypes with clinical phenotype. METHODS: This was a prospective, longitudinal (5 yr), multicenter, observational study. Inclusion criteria were less than 19 years at enrollment and greater than or equal to two annual study visits. Linear mixed effects models including random slope and random intercept were used to evaluate longitudinal associations between the ciliary defect group (or genotype group) and clinical features (percent predicted FEV and weight and height z-scores). MEASUREMENTS AND MAIN RESULTS: A total of 137 participants completed 732 visits. The group with absent inner dynein arm, central apparatus defects, and microtubular disorganization (IDA/CA/MTD) (n = 41) were significantly younger at diagnosis and in mixed effects models had significantly lower percent predicted FEV and weight and height z-scores than the isolated outer dynein arm defect (n = 55) group. Participants with CCDC39 or CCDC40 mutations (n = 34) had lower percent predicted FEV and weight and height z-scores than those with DNAH5 mutations (n = 36). For the entire cohort, percent predicted FEV decline was heterogeneous with a mean (SE) decline of 0.57 (0.25) percent predicted/yr. Rate of decline was different from zero only in the IDA/MTD/CA group (mean [SE], -1.11 [0.48] percent predicted/yr; P = 0.02). CONCLUSIONS: Participants with IDA/MTD/CA defects, which included individuals with CCDC39 or CCDC40 mutations, had worse lung function and growth indices compared with those with outer dynein arm defects and DNAH5 mutations, respectively. The only group with a significant lung function decline over time were participants with IDA/MTD/CA defects.
Keywords: Child; Cilia; Cohort Studies; Female; Genotype; Humans; Kartagener Syndrome; Longitudinal Studies; Lung; Male; Mutation; Phenotype; Prospective Studies; Respiratory Function Tests

Reanalysis of Clinical Exome Sequencing Data. - Liu, Pengfei; Meng, Linyan; Normand, Elizabeth A; Xia, Fan; Song, Xiaofei; Ghazi, Andrew; Rosenfeld, Jill; Magoulas, Pilar L; Braxton, Alicia; Ward, Patricia; Dai, Hongzheng; Yuan, Bo; et al. (N Engl J Med, 2019)
Keywords: Exome; Genetic Diseases, Inborn; Genetic Testing; Humans; Mutation; Phenotype; Sequence Analysis, DNA; Whole Exome Sequencing

Recessive DES cardio/myopathy without myofibrillar aggregates: intronic splice variant silences one allele leaving only missense L190P-desmin. - Riley, Lisa G; Waddell, Leigh B; Ghaoui, Roula; Evesson, Frances J; Cummings, Beryl B; Bryen, Samantha J; Joshi, Himanshu; Wang, Min-Xia; Brammah, Susan; Kritharides, Leonard; Corbett, Alastair; MacArthur, Daniel G; et al. (Eur J Hum Genet, 2019)
We establish autosomal recessive DES variants p.(Leu190Pro) and a deep intronic splice variant causing inclusion of a frameshift-inducing artificial exon/intronic fragment, as the likely cause of myopathy with cardiac involvement in female siblings. Both sisters presented in their twenties with slowly progressive limb girdle weakness, severe systolic dysfunction, and progressive, severe respiratory weakness. Desmin is an intermediate filament protein typically associated with autosomal dominant myofibrillar myopathy with cardiac involvement. However a few rare cases of autosomal recessive desminopathy are reported. In this family, a paternal missense p.(Leu190Pro) variant was viewed unlikely to be causative of autosomal dominant desminopathy, as the father and brothers carrying this variant were clinically unaffected. Clinical fit with a DES-related myopathy encouraged closer scrutiny of all DES variants, identifying a maternal deep intronic variant within intron-7, predicted to create a cryptic splice site, which segregated with disease. RNA sequencing and studies of muscle cDNA confirmed the deep intronic variant caused aberrant splicing of an artificial exon/intronic fragment into maternal DES mRNA transcripts, encoding a premature termination codon, and potently activating nonsense-mediate decay (92% paternal DES transcripts, 8% maternal). Western blot showed 60-75% reduction in desmin levels, likely comprised only of missense p.(Leu190Pro) desmin. Biopsy showed fibre size variation with increased central nuclei. Electron microscopy showed extensive myofibrillar disarray, duplication of the basal lamina, but no inclusions or aggregates. This study expands the phenotypic spectrum of recessive DES cardio/myopathy, and emphasizes the continuing importance of muscle biopsy for functional genomics pursuit of 'tricky' variants in neuromuscular conditions.

Recessive mutations in muscle-specific isoforms of FXR1 cause congenital multi-minicore myopathy. - Estañ, María Cristina; Fernández-Núñez, Elisa; Zaki, Maha S; Esteban, María Isabel; Donkervoort, Sandra; Hawkins, Cynthia; Caparros-Martin, José A; Saade, Dimah; Hu, Ying; Bolduc, Veronique; Chao, Katherine Ru-Yui; Nevado, Julián; et al. (Nat Commun, 2019)
FXR1 is an alternatively spliced gene that encodes RNA binding proteins (FXR1P) involved in muscle development. In contrast to other tissues, cardiac and skeletal muscle express two FXR1P isoforms that incorporate an additional exon-15. We report that recessive mutations in this particular exon of FXR1 cause congenital multi-minicore myopathy in humans and mice. Additionally, we show that while Myf5-dependent depletion of all FXR1P isoforms is neonatal lethal, mice carrying mutations in exon-15 display non-lethal myopathies which vary in severity depending on the specific effect of each mutation on the protein.
Keywords: Animals; Cells, Cultured; Exons; Gene Expression; Genes, Recessive; Genetic Predisposition to Disease; HEK293 Cells; HeLa Cells; Humans; Mice, Transgenic; Muscle, Skeletal; Mutation; Myopathies, Structural, Congenital; Ophthalmoplegia; RNA-Binding Proteins; Ryanodine Receptor Calcium Release Channel

A recurrent COL6A1 pseudoexon insertion causes muscular dystrophy and is effectively targeted by splice-correction therapies. - Bolduc, Veronique; Foley, A Reghan; Solomon-Degefa, Herimela; Sarathy, Apurva; Donkervoort, Sandra; Hu, Ying; Chen, Grace S; Sizov, Katherine; Nalls, Matthew; Zhou, Haiyan; Aguti, Sara; Cummings, Beryl B; et al. (JCI Insight, 2019)
The clinical application of advanced next-generation sequencing technologies is increasingly uncovering novel classes of mutations that may serve as potential targets for precision medicine therapeutics. Here, we show that a deep intronic splice defect in the COL6A1 gene, originally discovered by applying muscle RNA sequencing in patients with clinical findings of collagen VI-related dystrophy (COL6-RD), inserts an in-frame pseudoexon into COL6A1 mRNA, encodes a mutant collagen α1(VI) protein that exerts a dominant-negative effect on collagen VI matrix assembly, and provides a unique opportunity for splice-correction approaches aimed at restoring normal gene expression. Using splice-modulating antisense oligomers, we efficiently skipped the pseudoexon in patient-derived fibroblast cultures and restored a wild-type matrix. Similarly, we used CRISPR/Cas9 to precisely delete an intronic sequence containing the pseudoexon and efficiently abolish its inclusion while preserving wild-type splicing. Considering that this splice defect is emerging as one of the single most frequent mutations in COL6-RD, the design of specific and effective splice-correction therapies offers a promising path for clinical translation.

Redefining the Etiologic Landscape of Cerebellar Malformations. - Aldinger, Kimberly A; Timms, Andrew E; Thomson, Zachary; Mirzaa, Ghayda M; Bennett, James T; Rosenberg, Alexander B; Roco, Charles M; Hirano, Matthew; Abidi, Fatima; Haldipur, Parthiv; Cheng, Chi V; Collins, Sarah; et al. (Am J Hum Genet, 2019)
Cerebellar malformations are diverse congenital anomalies frequently associated with developmental disability. Although genetic and prenatal non-genetic causes have been described, no systematic analysis has been performed. Here, we present a large-exome sequencing study of Dandy-Walker malformation (DWM) and cerebellar hypoplasia (CBLH). We performed exome sequencing in 282 individuals from 100 families with DWM or CBLH, and we established a molecular diagnosis in 36 of 100 families, with a significantly higher yield for CBLH (51%) than for DWM (16%). The 41 variants impact 27 neurodevelopmental-disorder-associated genes, thus demonstrating that CBLH and DWM are often features of monogenic neurodevelopmental disorders. Though only seven monogenic causes (19%) were identified in more than one individual, neuroimaging review of 131 additional individuals confirmed cerebellar abnormalities in 23 of 27 genetic disorders (85%). Prenatal risk factors were frequently found among individuals without a genetic diagnosis (30 of 64 individuals [47%]). Single-cell RNA sequencing of prenatal human cerebellar tissue revealed gene enrichment in neuronal and vascular cell types; this suggests that defective vasculogenesis may disrupt cerebellar development. Further, de novo gain-of-function variants in PDGFRB, a tyrosine kinase receptor essential for vascular progenitor signaling, were associated with CBLH, and this discovery links genetic and non-genetic etiologies. Our results suggest that genetic defects impact specific cerebellar cell types and implicate abnormal vascular development as a mechanism for cerebellar malformations. We also confirmed a major contribution for non-genetic prenatal factors in individuals with cerebellar abnormalities, substantially influencing diagnostic evaluation and counseling regarding recurrence risk and prognosis.

A retrospective analysis of the prevalence of imprinting disorders in Estonia from 1998 to 2016. - Yakoreva, Maria; Kahre, Tiina; Žordania, Riina; Reinson, Karit; Teek, Rita; Tillmann, Vallo; Peet, Aleksandr; Õiglane-Shlik, Eve; Pajusalu, Sander; Murumets, Ülle; Vals, Mari-Anne; Mee, Pille; et al. (Eur J Hum Genet, 2019)
Imprinting disorders (ImpDis) represent a small group of rare congenital diseases primarily affecting growth, development, and the hormonal and metabolic systems. The aim of present study was to identify the prevalence of the ImpDis in Estonia, to describe trends in the live birth prevalence of these disorders between 1998 and 2016, and to compare the results with previously published data. We retrospectively reviewed the records of all Estonian patients since 1998 with both molecularly and clinically diagnosed ImpDis. A prospective study was also conducted, in which all patients with clinical suspicion for an ImpDis were molecularly analyzed. Eighty-seven individuals with ImpDis were identified. Twenty-seven (31%) of them had Prader-Willi syndrome (PWS), 15 (17%) had Angelman syndrome (AS), 15 (17%) had Silver-Russell syndrome (SRS), 12 (14%) had Beckwith-Wiedemann syndrome (BWS), 10 (11%) had pseudo- or pseudopseudohypoparathyroidism, four had central precocious puberty, two had Temple syndrome, one had transient neonatal diabetes mellitus, and one had myoclonus-dystonia syndrome. One third of SRS and BWS cases fulfilled the diagnostic criteria for these disorders, but tested negative for genetic abnormalities. Seventy-six individuals were alive as of January 1, 2018, indicating the total prevalence of ImpDis in Estonia is 5.8/100,000 (95% CI 4.6/100,000-7.2/100,000). The minimum live birth prevalence of all ImpDis in Estonia in 2004-2016 was 1/3,462, PWS 1/13,599, AS 1/27,198, BWS 1/21,154, SRS 1/15,866, and PHP/PPHP 1/27,198. Our results are only partially consistent with previously published data. The worldwide prevalence of SRS and GNAS-gene-related ImpDis is likely underestimated and may be at least three times higher than expected.

ROBO4 variants predispose individuals to bicuspid aortic valve and thoracic aortic aneurysm. - Gould, Russell A; Aziz, Hamza; Woods, Courtney E; Seman-Senderos, Manuel Alejandro; Sparks, Elizabeth; Preuss, Christoph; Wünnemann, Florian; Bedja, Djahida; Moats, Cassandra R; McClymont, Sarah A; Rose, Rebecca; Sobreira, Nara; et al. (Nat Genet, 2019)
Bicuspid aortic valve (BAV) is a common congenital heart defect (population incidence, 1-2%) that frequently presents with ascending aortic aneurysm (AscAA). BAV/AscAA shows autosomal dominant inheritance with incomplete penetrance and male predominance. Causative gene mutations (for example, NOTCH1, SMAD6) are known for ≤1% of nonsyndromic BAV cases with and without AscAA, impeding mechanistic insight and development of therapeutic strategies. Here, we report the identification of variants in ROBO4 (which encodes a factor known to contribute to endothelial performance) that segregate with disease in two families. Targeted sequencing of ROBO4 showed enrichment for rare variants in BAV/AscAA probands compared with controls. Targeted silencing of ROBO4 or mutant ROBO4 expression in endothelial cell lines results in impaired barrier function and a synthetic repertoire suggestive of endothelial-to-mesenchymal transition. This is consistent with BAV/AscAA-associated findings in patients and in animal models deficient for ROBO4. These data identify a novel endothelial etiology for this common human disease phenotype.
Keywords: Animals; Aortic Aneurysm, Thoracic; Aortic Valve; Cells, Cultured; Disease Models, Animal; Endothelial Cells; Female; Heart Valve Diseases; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Receptors, Cell Surface; Zebrafish

SMAD4 rare variants in individuals and families with thoracic aortic aneurysms and dissections. - Duan, Xue-Yan; Guo, Dong-Chuan; Regalado, Ellen S; Shen, Hong; Coselli, Joseph S; Estrera, Anthony L; Safi, Hazim J; Bamshad, Michael J; Nickerson, Deborah A; LeMaire, Scott A; De Backer, Julie; Milewicz, Dianna M (Eur J Hum Genet, 2019)
SMAD4 pathogenic variants cause juvenile polyposis (JPS) and hereditary hemorrhagic telangiectasia (HHT), and 40% of affected individuals also have thoracic aortic disease. At the same time, SMAD4 pathogenic variants have not been reported in thoracic aortic disease families without JPS-HHT. A SMAD4 heterozygous variant, c.290G>T, p.(Arg97Leu), not present in population databases and predicted to be damaging to protein function, was identified in a family with thoracic aortic disease and no evidence of HHT or JPS. Cellular studies revealed that the SMAD4 p.(Arg97Leu) alteration increased SMAD4 ubiquitination and 26S proteasome-mediated protein degradation. Smooth muscle cells (SMCs) infected with lentivirus expressing the SMAD4 p.(Arg97Leu) variant demonstrated reduced contractile protein gene expression when compared to that of wild-type SMAD4. In addition, two rare variants were identified in individuals with early age of onset of thoracic aortic dissection. These results suggest that SMAD4 rare missense variants can lead to thoracic aortic disease in individuals who do not have JPS or HHT.

Spatially clustering de novo variants in CYFIP2, encoding the cytoplasmic FMRP interacting protein 2, cause intellectual disability and seizures. - Zweier, Markus; Begemann, Anaïs; McWalter, Kirsty; Cho, Megan T; Abela, Lucia; Banka, Siddharth; Behring, Bettina; Berger, Andrea; Brown, Chester W; Carneiro, Maryline; Chen, Jiani; Cooper, Gregory M; et al. (Eur J Hum Genet, 2019)
CYFIP2, encoding the evolutionary highly conserved cytoplasmic FMRP interacting protein 2, has previously been proposed as a candidate gene for intellectual disability and autism because of its important role linking FMRP-dependent transcription regulation and actin polymerization via the WAVE regulatory complex (WRC). Recently, de novo variants affecting the amino acid p.Arg87 of CYFIP2 were reported in four individuals with epileptic encephalopathy. We here report 12 independent patients harboring a variety of de novo variants in CYFIP2 broadening the molecular and clinical spectrum of a novel CYFIP2-related neurodevelopmental disorder. Using trio whole-exome or -genome sequencing, we identified 12 independent patients carrying a total of eight distinct de novo variants in CYFIP2 with a shared phenotype of intellectual disability, seizures, and muscular hypotonia. We detected seven different missense variants, of which two occurred recurrently (p.(Arg87Cys) and p.(Ile664Met)), and a splice donor variant in the last intron for which we showed exon skipping in the transcript. The latter is expected to escape nonsense-mediated mRNA decay resulting in a truncated protein. Despite the large spacing in the primary structure, the variants spatially cluster in the tertiary structure and are all predicted to weaken the interaction with WAVE1 or NCKAP1 of the actin polymerization regulating WRC-complex. Preliminary genotype-phenotype correlation indicates a profound phenotype in p.Arg87 substitutions and a more variable phenotype in other alterations. This study evidenced a variety of de novo variants in CYFIP2 as a novel cause of mostly severe intellectual disability with seizures and muscular hypotonia.

Targeted Treatment of Individuals With Psychosis Carrying a Copy Number Variant Containing a Genomic Triplication of the Glycine Decarboxylase Gene. - Bodkin, J Alexander; Coleman, Michael J; Godfrey, Laura J; Carvalho, Claudia M B; Morgan, Charity J; Suckow, Raymond F; Anderson, Thea; Öngür, Dost; Kaufman, Marc J; Lewandowski, Kathryn E; Siegel, Arthur J; Waldstreicher, Elliot; et al. (Biol Psychiatry, 2019)
BACKGROUND: The increased mutational burden for rare structural genomic variants in schizophrenia and other neurodevelopmental disorders has so far not yielded therapies targeting the biological effects of specific mutations. We identified two carriers (mother and son) of a triplication of the gene encoding glycine decarboxylase, GLDC, presumably resulting in reduced availability of the N-methyl-D-aspartate receptor coagonists glycine and D-serine and N-methyl-D-aspartate receptor hypofunction. Both carriers had a diagnosis of a psychotic disorder. METHODS: We carried out two double-blind, placebo-controlled clinical trials of N-methyl-D-aspartate receptor augmentation of psychotropic drug treatment in these two individuals. Glycine was used in the first clinical trial, and D-cycloserine was used in the second one. RESULTS: Glycine or D-cycloserine augmentation of psychotropic drug treatment each improved psychotic and mood symptoms in placebo-controlled trials. CONCLUSIONS: These results provide two independent proof-of-principle demonstrations of symptom relief by targeting a specific genotype and explicitly link an individual mutation to the pathophysiology of psychosis and treatment response.

TBX6 compound inheritance leads to congenital vertebral malformations in humans and mice. - Yang, Nan; Wu, Nan; Zhang, Ling; Zhao, Yanxue; Liu, Jiaqi; Liang, Xiangyu; Ren, Xiaojun; Li, Weiyu; Chen, Weisheng; Dong, Shuangshuang; Zhao, Sen; Lin, Jiachen; et al. (Hum Mol Genet, 2019)
Congenital vertebral malformations (CVMs) are associated with human TBX6 compound inheritance that combines a rare null allele and a common hypomorphic allele at the TBX6 locus. Our previous in vitro evidence suggested that this compound inheritance resulted in a TBX6 gene dosage of less than haploinsufficiency (i.e. <50%) as a potential mechanism of TBX6-associated CVMs. To further investigate this pathogenetic model, we ascertained and collected 108 Chinese CVM cases and found that 10 (9.3%) of them carried TBX6 null mutations in combination with common hypomorphic variants at the second TBX6 allele. For in vivo functional verification and genetic analysis of TBX6 compound inheritance, we generated both null and hypomorphic mutations in mouse Tbx6 using the CRISPR-Cas9 method. These Tbx6 mutants are not identical to the patient variants at the DNA sequence level, but instead functionally mimic disease-associated TBX6 variants. Intriguingly, as anticipated by the compound inheritance model, a high penetrance of CVM phenotype was only observed in the mice with combined null and hypomorphic alleles of Tbx6. These findings are consistent with our experimental observations in humans and supported the dosage effect of TBX6 in CVM etiology. In conclusion, our findings in the newly collected human CVM subjects and Tbx6 mouse models consistently support the contention that TBX6 compound inheritance causes CVMs, potentially via a gene dosage-dependent mechanism. Furthermore, mouse Tbx6 mutants mimicking human CVM-associated variants will be useful models for further mechanistic investigations of CVM pathogenesis in the cases associated with TBX6.
Keywords: Adolescent; Alleles; Animals; Child; Child, Preschool; Congenital Abnormalities; CRISPR-Cas Systems; Disease Models, Animal; Female; Haploinsufficiency; Humans; Infant; Male; Mice; Mutation; Phenotype; Scoliosis; Spine; T-Box Domain Proteins

TBX6-associated congenital scoliosis (TACS) as a clinically distinguishable subtype of congenital scoliosis: further evidence supporting the compound inheritance and TBX6 gene dosage model. - Liu, Jiaqi; Wu, Nan; Yang, Nan; Takeda, Kazuki; Chen, Weisheng; Li, Weiyu; Du, Renqian; Liu, Sen; Zhou, Yangzhong; Zhang, Ling; Liu, Zhenlei; Zuo, Yuzhi; et al. (Genet Med, 2019)
PURPOSE: To characterize clinically measurable endophenotypes, implicating the TBX6 compound inheritance model. METHODS: Patients with congenital scoliosis (CS) from China(N = 345, cohort 1), Japan (N = 142, cohort 2), and the United States (N = 10, cohort 3) were studied. Clinically measurable endophenotypes were compared according to the TBX6 genotypes. A mouse model for Tbx6 compound inheritance (N = 52) was investigated by micro computed tomography (micro-CT). A clinical diagnostic algorithm (TACScore) was developed to assist in clinical recognition of TBX6-associated CS (TACS). RESULTS: In cohort 1, TACS patients (N = 33) were significantly younger at onset than the remaining CS patients (P = 0.02), presented with one or more hemivertebrae/butterfly vertebrae (P = 4.9 × 10), and exhibited vertebral malformations involving the lower part of the spine (T8-S5, P = 4.4 × 10); observations were confirmed in two replication cohorts. Simple rib anomalies were prevalent in TACS patients (P = 3.1 × 10), while intraspinal anomalies were uncommon (P = 7.0 × 10). A clinically usable TACScore was developed with an area under the curve (AUC) of 0.9 (P = 1.6 × 10). A Tbx6 mouse model supported that a gene dosage effect underlies the TACS phenotype. CONCLUSION: TACS is a clinically distinguishable entity with consistent clinically measurable endophenotypes. The type and distribution of vertebral column abnormalities in TBX6/Tbx6 compound inheritance implicate subtle perturbations in gene dosage as a cause of spine developmental birth defects responsible for about 10% of CS.

Ten years of Genome Medicine. - Auffray, Charles; Griffin, Julian L; Khoury, Muin J; Lupski, James R; Schwab, Matthias (Genome Med, 2019)
Keywords: Genomics; History, 21st Century; Human Genetics; Humans; Periodicals as Topic

Unique bioinformatic approach and comprehensive reanalysis improve diagnostic yield of clinical exomes. - Schmitz-Abe, Klaus; Li, Qifei; Rosen, Samantha M; Nori, Neeharika; Madden, Jill A; Genetti, Casie A; Wojcik, Monica H; Ponnaluri, Sadhana; Gubbels, Cynthia S; Picker, Jonathan D; O'Donnell-Luria, Anne H; Yu, Timothy W; et al. (Eur J Hum Genet, 2019)
Clinical exome sequencing (CES) is increasingly being utilized; however, a large proportion of patients remain undiagnosed, creating a need for a systematic approach to increase the diagnostic yield. We have reanalyzed CES data for a clinically heterogeneous cohort of 102 probands with likely Mendelian conditions, including 74 negative cases and 28 cases with candidate variants, but reanalysis requested by clinicians. Reanalysis was performed by an interdisciplinary team using a validated custom-built pipeline, "Variant Explorer Pipeline" (VExP). This reanalysis approach and results were compared with existing literature. Reanalysis of candidate variants from CES in 28 cases revealed 1 interpretation that needed to be reclassified. A confirmed or potential genetic diagnosis was identified in 24 of 75 CES-negative/reclassified cases (32.0%), including variants in known disease-causing genes (n = 6) or candidate genes (n = 18). This yield was higher compared with similar studies demonstrating the utility of this approach. In summary, reanalysis of negative CES in a research setting enhances diagnostic yield by about a third. This study suggests the need for comprehensive, continued reanalysis of exome data when molecular diagnosis is elusive.

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly. - Ullah, Irfan; Kakar, Naseebullah; Schrauwen, Isabelle; Hussain, Shabir; Chakchouk, Imen; Liaqat, Khurram; Acharya, Anushree; Wasif, Naveed; Santos-Cortez, Regie Lyn P; Khan, Saadullah; Aziz, Abdul; Lee, Kwanghyuk; et al. (Hum Genet, 2019)
Postaxial polydactyly (PAP) is a common limb malformation that often leads to cosmetic and functional complications. Molecular evaluation of polydactyly can serve as a tool to elucidate genetic and signaling pathways that regulate limb development, specifically, the anterior-posterior specification of the limb. To date, only five genes have been identified for nonsyndromic PAP: FAM92A, GLI1, GLI3, IQCE and ZNF141. In this study, two Pakistani multiplex consanguineous families with autosomal recessive nonsyndromic PAP were clinically and molecularly evaluated. From both pedigrees, a DNA sample from an affected member underwent exome sequencing. In each family, we identified a segregating frameshift (c.591dupA [p.(Q198Tfs*21)]) and nonsense variant (c.2173A > T [p.(K725*)]) in KIAA0825 (also known as C5orf36). Although KIAA0825 encodes a protein of unknown function, it has been demonstrated that its murine ortholog is expressed during limb development. Our data contribute to the establishment of a catalog of genes important in limb patterning, which can aid in diagnosis and obtaining a better understanding of the biology of polydactyly.
Keywords: Animals; Consanguinity; Family Health; Female; Fingers; Genes, Recessive; Genetic Predisposition to Disease; Genotype; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice, Inbred C57BL; Mutation; Pedigree; Phenotype; Polydactyly; Toes; Whole Exome Sequencing

Whole-Exome Sequencing Enables a Precision Medicine Approach for Kidney Transplant Recipients. - Mann, Nina; Braun, Daniela A; Amann, Kassaundra; Tan, Weizhen; Shril, Shirlee; Connaughton, Dervla M; Nakayama, Makiko; Schneider, Ronen; Kitzler, Thomas M; van der Ven, Amelie T; Chen, Jing; Ityel, Hadas; et al. (J Am Soc Nephrol, 2019)
BACKGROUND: Whole-exome sequencing (WES) finds a CKD-related mutation in approximately 20% of patients presenting with CKD before 25 years of age. Although provision of a molecular diagnosis could have important implications for clinical management, evidence is lacking on the diagnostic yield and clinical utility of WES for pediatric renal transplant recipients. METHODS: To determine the diagnostic yield of WES in pediatric kidney transplant recipients, we recruited 104 patients who had received a transplant at Boston Children's Hospital from 2007 through 2017, performed WES, and analyzed results for likely deleterious variants in approximately 400 genes known to cause CKD. RESULTS: By WES, we identified a genetic cause of CKD in 34 out of 104 (32.7%) transplant recipients. The likelihood of detecting a molecular genetic diagnosis was highest for patients with urinary stone disease (three out of three individuals), followed by renal cystic ciliopathies (seven out of nine individuals), steroid-resistant nephrotic syndrome (nine out of 21 individuals), congenital anomalies of the kidney and urinary tract (ten out of 55 individuals), and chronic glomerulonephritis (one out of seven individuals). WES also yielded a molecular diagnosis for four out of nine individuals with ESRD of unknown etiology. The WES-related molecular genetic diagnosis had implications for clinical care for five patients. CONCLUSIONS: Nearly one third of pediatric renal transplant recipients had a genetic cause of their kidney disease identified by WES. Knowledge of this genetic information can help guide management of both transplant patients and potential living related donors.
Keywords: Adolescent; Boston; Child; Child, Preschool; Cohort Studies; Female; Genetic Predisposition to Disease; Genetic Testing; Graft Rejection; Graft Survival; Hospitals, Pediatric; Humans; Kidney Transplantation; Male; Precision Medicine; Prognosis; Renal Insufficiency, Chronic; Retrospective Studies; Risk Assessment; Severity of Illness Index; Survival Analysis; Transplant Recipients; Treatment Outcome; Whole Exome Sequencing

ZMIZ1 Variants Cause a Syndromic Neurodevelopmental Disorder. - Carapito, Raphael; Ivanova, Ekaterina L; Morlon, Aurore; Meng, Linyan; Molitor, Anne; Erdmann, Eva; Kieffer, Bruno; Pichot, Angélique; Naegely, Lydie; Kolmer, Aline; Paul, Nicodème; Hanauer, Antoine; et al. (Am J Hum Genet, 2019)
ZMIZ1 is a coactivator of several transcription factors, including p53, the androgen receptor, and NOTCH1. Here, we report 19 subjects with intellectual disability and developmental delay carrying variants in ZMIZ1. The associated features include growth failure, feeding difficulties, microcephaly, facial dysmorphism, and various other congenital malformations. Of these 19, 14 unrelated subjects carried de novo heterozygous single-nucleotide variants (SNVs) or single-base insertions/deletions, 3 siblings harbored a heterozygous single-base insertion, and 2 subjects had a balanced translocation disrupting ZMIZ1 or involving a regulatory region of ZMIZ1. In total, we identified 13 point mutations that affect key protein regions, including a SUMO acceptor site, a central disordered alanine-rich motif, a proline-rich domain, and a transactivation domain. All identified variants were absent from all available exome and genome databases. In vitro, ZMIZ1 showed impaired coactivation of the androgen receptor. In vivo, overexpression of ZMIZ1 mutant alleles in developing mouse brains using in utero electroporation resulted in abnormal pyramidal neuron morphology, polarization, and positioning, underscoring the importance of ZMIZ1 in neural development and supporting mutations in ZMIZ1 as the cause of a rare neurodevelopmental syndrome.
Keywords: Alleles; Animals; Child; Child, Preschool; Developmental Disabilities; Female; Humans; Infant; Intellectual Disability; Male; Mice; Point Mutation; Syndrome; Transcription Factors

Additional features of Gillespie syndrome in two Brazilian siblings with a novel ITPR1 homozygous pathogenic variant. - Carvalho, Daniel R; Medeiros, João Eugenio G; Ribeiro, Daniela Sebestyan M; Martins, Bernardo J A F; Sobreira, Nara L M (Eur J Med Genet, 2018)
Gillespie syndrome (GS) [MIM: 206700] is a very rare condition characterized by bilateral iris defect, congenital hypotonia, cerebellar ataxia and intellectual disability. The typical iris anomaly is considered necessary to the diagnosis of GS. Recently, variants in ITPR1 were described causing GS. Non-neurological features were reported in few patients. Here we describe two consanguineous siblings with GS and a novel homozygous ITPR1 pathogenic variant (p.N984fs). They also present a cardiac defect (pulmonary valve stenosis) and one sib had a genitourinary malformation (ureteropelvic junction obstruction). Our report reinforces ITPR1 as the cause of GS and suggests a possible role of ITPR1 in the development of other organs.
Keywords: Aniridia; Brazil; Cerebellar Ataxia; Child, Preschool; Consanguinity; Female; Homozygote; Humans; Infant; Inositol 1,4,5-Trisphosphate Receptors; Intellectual Disability; Male; Mutation; Pedigree; Siblings

Analyses of LMNA-negative juvenile progeroid cases confirms biallelic POLR3A mutations in Wiedemann-Rautenstrauch-like syndrome and expands the phenotypic spectrum of PYCR1 mutations. - Lessel, Davor; Ozel, Ayse Bilge; Campbell, Susan E; Saadi, Abdelkrim; Arlt, Martin F; McSweeney, Keisha Melodi; Plaiasu, Vasilica; Szakszon, Katalin; Szőllős, Anna; Rusu, Cristina; Rojas, Armando J; Lopez-Valdez, Jaime; et al. (Hum Genet, 2018)
Juvenile segmental progeroid syndromes are rare, heterogeneous disorders characterized by signs of premature aging affecting more than one tissue or organ starting in childhood. Hutchinson-Gilford progeria syndrome (HGPS), caused by a recurrent de novo synonymous LMNA mutation resulting in aberrant splicing and generation of a mutant product called progerin, is a prototypical example of such disorders. Here, we performed a joint collaborative study using massively parallel sequencing and targeted Sanger sequencing, aimed at delineating the underlying genetic cause of 14 previously undiagnosed, clinically heterogeneous, non-LMNA-associated juvenile progeroid patients. The molecular diagnosis was achieved in 11 of 14 cases (~ 79%). Furthermore, we firmly establish biallelic mutations in POLR3A as the genetic cause of a recognizable, neonatal, Wiedemann-Rautenstrauch-like progeroid syndrome. Thus, we suggest that POLR3A mutations are causal for a portion of under-diagnosed early-onset segmental progeroid syndromes. We additionally expand the clinical spectrum associated with PYCR1 mutations by showing that they can somewhat resemble HGPS in the first year of life. Moreover, our results lead to clinical reclassification in one single case. Our data emphasize the complex genetic and clinical heterogeneity underlying progeroid disorders.
Keywords: Adolescent; Alternative Splicing; Child; Female; Fetal Growth Retardation; Genetic Predisposition to Disease; Humans; Infant; Lamin Type A; Male; Mutation; Phenotype; Progeria; Pyrroline Carboxylate Reductases; RNA Polymerase III

Analysis of 17 genes detects mutations in 81% of 811 patients with lissencephaly. - Di Donato, Nataliya; Timms, Andrew E; Aldinger, Kimberly A; Mirzaa, Ghayda M; Bennett, James T; Collins, Sarah; Olds, Carissa; Mei, Davide; Chiari, Sara; Carvill, Gemma; Myers, Candace T; Rivière, Jean-Baptiste; et al. (Genet Med, 2018)
PURPOSE: To estimate diagnostic yield and genotype-phenotype correlations in a cohort of 811 patients with lissencephaly or subcortical band heterotopia. METHODS: We collected DNA from 756 children with lissencephaly over 30 years. Many were tested for deletion 17p13.3 and mutations of LIS1, DCX, and ARX, but few other genes. Among those tested, 216 remained unsolved and were tested by a targeted panel of 17 genes (ACTB, ACTG1, ARX, CRADD, DCX, LIS1, TUBA1A, TUBA8, TUBB2B, TUBB, TUBB3, TUBG1, KIF2A, KIF5C, DYNC1H1, RELN, and VLDLR) or by whole-exome sequencing. Fifty-five patients studied at another institution were added as a validation cohort. RESULTS: The overall mutation frequency in the entire cohort was 81%. LIS1 accounted for 40% of patients, followed by DCX (23%), TUBA1A (5%), and DYNC1H1 (3%). Other genes accounted for 1% or less of patients. Nineteen percent remained unsolved, which suggests that several additional genes remain to be discovered. The majority of unsolved patients had posterior pachygyria, subcortical band heterotopia, or mild frontal pachygyria. CONCLUSION: The brain-imaging pattern correlates with mutations in single lissencephaly-associated genes, as well as in biological pathways. We propose the first LIS classification system based on the underlying molecular mechanisms.
Keywords: Brain; Classical Lissencephalies and Subcortical Band Heterotopias; DNA Mutational Analysis; Female; Genetic Association Studies; Humans; Lissencephaly; Male; Mutation; Whole Exome Sequencing

and Mutations Implicate RAB5 Regulation in Nephrotic Syndrome. - Hermle, Tobias; Schneider, Ronen; Schapiro, David; Braun, Daniela A; van der Ven, Amelie T; Warejko, Jillian K; Daga, Ankana; Widmeier, Eugen; Nakayama, Makiko; Jobst-Schwan, Tilman; Majmundar, Amar J; Ashraf, Shazia; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Steroid-resistant nephrotic syndrome (SRNS) is a frequent cause of CKD. The discovery of monogenic causes of SRNS has revealed specific pathogenetic pathways, but these monogenic causes do not explain all cases of SRNS. METHODS: To identify novel monogenic causes of SRNS, we screened 665 patients by whole-exome sequencing. We then evaluated the functional significance of two genes and the mutations therein that we discovered through this sequencing and conducted complementary studies in podocyte-like nephrocytes. RESULTS: We identified conserved, homozygous missense mutations of in two families with early-onset NS and a homozygous missense mutation of in two siblings with SRNS. GAPVD1 and ANKFY1 interact with the endosomal regulator RAB5. Coimmunoprecipitation assays indicated interaction between GAPVD1 and ANKFY1 proteins, which also colocalized when expressed in HEK293T cells. Silencing either protein diminished the podocyte migration rate. Compared with wild-type GAPVD1 and ANKFY1, the mutated proteins produced upon ectopic expression of or bearing the patient-derived mutations exhibited altered binding affinity for active RAB5 and reduced ability to rescue the knockout-induced defect in podocyte migration. Coimmunoprecipitation assays further demonstrated a physical interaction between nephrin and GAPVD1, and immunofluorescence revealed partial colocalization of these proteins in rat glomeruli. The patient-derived mutations reduced nephrin-GAPVD1 binding affinity. In , silencing impaired endocytosis and caused mistrafficking of the nephrin ortholog. CONCLUSIONS: Mutations in and probably in are novel monogenic causes of NS. The discovery of these genes implicates RAB5 regulation in the pathogenesis of human NS.

Ari-1 Regulates Myonuclear Organization Together with Parkin and Is Associated with Aortic Aneurysms. - Tan, Kai Li; Haelterman, Nele A; Kwartler, Callie S; Regalado, Ellen S; Lee, Pei-Tseng; Nagarkar-Jaiswal, Sonal; Guo, Dong-Chuan; Duraine, Lita; Wangler, Michael F; Bamshad, Michael J; Nickerson, Deborah A; Lin, Guang; et al. (Dev Cell, 2018)
Nuclei are actively positioned and anchored to the cytoskeleton via the LINC (Linker of Nucleoskeleton and Cytoskeleton) complex. We identified mutations in the Parkin-like E3 ubiquitin ligase Ariadne-1 (Ari-1) that affect the localization and distribution of LINC complex members in Drosophila. ari-1 mutants exhibit nuclear clustering and morphology defects in larval muscles. We show that Ari-1 mono-ubiquitinates the core LINC complex member Koi. Surprisingly, we discovered functional redundancy between Parkin and Ari-1: increasing Parkin expression rescues ari-1 mutant phenotypes and vice versa. We further show that rare variants in the human homolog of ari-1 (ARIH1) are associated with thoracic aortic aneurysms and dissections, conditions resulting from smooth muscle cell (SMC) dysfunction. Human ARIH1 rescues fly ari-1 mutant phenotypes, whereas human variants found in patients fail to do so. In addition, SMCs obtained from patients display aberrant nuclear morphology. Hence, ARIH1 is critical in anchoring myonuclei to the cytoskeleton.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Animals; Aortic Aneurysm; Carrier Proteins; Cell Nucleus; Child, Preschool; Cytoskeleton; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Male; Middle Aged; Mutation; Myocytes, Smooth Muscle; Pedigree; Phenotype; Ubiquitin-Protein Ligases; Young Adult

Autosomal recessive Stickler syndrome resulting from a COL9A3 mutation. - Hanson-Kahn, Andrea; Li, Bing; Cohn, Daniel H; Nickerson, Deborah A; Bamshad, Michael J; Hudgins, Louanne (Am J Med Genet A, 2018)
Stickler syndrome is a connective tissue disorder characterized by hearing loss, ocular anomalies, palatal defects, and skeletal abnormalities. The autosomal dominant form is the most common, but autosomal recessive forms have also been described. We report the second case of autosomal recessive Stickler syndrome due to homozygosity for a loss of function mutation in COL9A3, which encodes the α3 chain of type IX procollagen. The clinical features were similar to the previously described COL9A3 Stickler syndrome family, including moderate to severe sensorineural hearing loss, high myopia, and both tibial and femoral bowing at birth. Radiographs demonstrated abnormal capital femoral epiphyses and mild irregularities of the vertebral endplates. This case further establishes the phenotype associated with mutations in this gene. We suggest that loss of the α3 chain of type IX collagen results in a Stickler syndrome phenotype similar to that of the other autosomal recessive forms caused by mutations in genes encoding the α1 and α2 chains of type IX collagen.

A biallelic ANTXR1 variant expands the anthrax toxin receptor associated phenotype to tooth agenesis. - Dinckan, Nuriye; Du, Renqian; Akdemir, Zeynep C; Bayram, Yavuz; Jhangiani, Shalini N; Doddapaneni, Harsha; Hu, Jianhong; Muzny, Donna M; Guven, Yeliz; Aktoren, Oya; Kayserili, Hülya; Boerwinkle, Eric; et al. (Am J Med Genet A, 2018)
Tooth development is regulated by multiple genetic pathways, which ultimately drive the complex interactions between the oral epithelium and mesenchyme. Disruptions at any time point during this process may lead to failure of tooth development, also known as tooth agenesis (TA). TA is a common craniofacial abnormality in humans and represents the failure to develop one or more permanent teeth. Many genes and potentially subtle variants in these genes contribute to the TA phenotype. We report the clinical and genetic impact of a rare homozygous ANTXR1 variant (c.1312C>T), identified by whole exome sequencing (WES), in a consanguineous Turkish family with TA. Mutations in ANTXR1 have been associated with GAPO (growth retardation, alopecia, pseudoanodontia, and optic atrophy) syndrome and infantile hemangioma, however no clinical characteristics associated with these conditions were observed in our study family. We detected the expression of Antxr1 in oral and dental tissues of developing mouse embryos, further supporting a role for this gene in tooth development. Our findings implicate ANTXR1 as a candidate gene for isolated TA, suggest the involvement of specific hypomorphic alleles, and expand the previously known ANTXR1-associated phenotypes.
Keywords: Alleles; Amino Acid Substitution; Animals; Anodontia; Child; Consanguinity; Facies; Genetic Association Studies; Genotype; Humans; Male; Mice; Mutation; Neoplasm Proteins; Pedigree; Phenotype; Radiography; Receptors, Cell Surface; Whole Exome Sequencing

Bi-allelic CCDC47 Variants Cause a Disorder Characterized by Woolly Hair, Liver Dysfunction, Dysmorphic Features, and Global Developmental Delay. - Morimoto, Marie; Waller-Evans, Helen; Ammous, Zineb; Song, Xiaofei; Strauss, Kevin A; Pehlivan, Davut; Gonzaga-Jauregui, Claudia; Puffenberger, Erik G; Holst, Charles R; Karaca, Ender; Brigatti, Karlla W; Maguire, Emily; et al. (Am J Hum Genet, 2018)
Ca signaling is vital for various cellular processes including synaptic vesicle exocytosis, muscle contraction, regulation of secretion, gene transcription, and cellular proliferation. The endoplasmic reticulum (ER) is the largest intracellular Ca store, and dysregulation of ER Ca signaling and homeostasis contributes to the pathogenesis of various complex disorders and Mendelian disease traits. We describe four unrelated individuals with a complex multisystem disorder characterized by woolly hair, liver dysfunction, pruritus, dysmorphic features, hypotonia, and global developmental delay. Through whole-exome sequencing and family-based genomics, we identified bi-allelic variants in CCDC47 that encodes the Ca-binding ER transmembrane protein CCDC47. CCDC47, also known as calumin, has been shown to bind Ca with low affinity and high capacity. In mice, loss of Ccdc47 leads to embryonic lethality, suggesting that Ccdc47 is essential for early development. Characterization of cells from individuals with predicted likely damaging alleles showed decreased CCDC47 mRNA expression and protein levels. In vitro cellular experiments showed decreased total ER Ca storage, impaired Ca signaling mediated by the IPR Ca release channel, and reduced ER Ca refilling via store-operated Ca entry. These results, together with the previously described role of CCDC47 in Ca signaling and development, suggest that bi-allelic loss-of-function variants in CCDC47 underlie the pathogenesis of this multisystem disorder.

Biallelic Mutations in ADPRHL2, Encoding ADP-Ribosylhydrolase 3, Lead to a Degenerative Pediatric Stress-Induced Epileptic Ataxia Syndrome. - Ghosh, Shereen G; Becker, Kerstin; Huang, He; Dixon-Salazar, Tracy; Chai, Guoliang; Salpietro, Vincenzo; Al-Gazali, Lihadh; Waisfisz, Quinten; Wang, Haicui; Vaux, Keith K; Stanley, Valentina; Manole, Andreea; et al. (Am J Hum Genet, 2018)
ADP-ribosylation, the addition of poly-ADP ribose (PAR) onto proteins, is a response signal to cellular challenges, such as excitotoxicity or oxidative stress. This process is catalyzed by a group of enzymes referred to as poly(ADP-ribose) polymerases (PARPs). Because the accumulation of proteins with this modification results in cell death, its negative regulation restores cellular homeostasis: a process mediated by poly-ADP ribose glycohydrolases (PARGs) and ADP-ribosylhydrolase proteins (ARHs). Using linkage analysis and exome or genome sequencing, we identified recessive inactivating mutations in ADPRHL2 in six families. Affected individuals exhibited a pediatric-onset neurodegenerative disorder with progressive brain atrophy, developmental regression, and seizures in association with periods of stress, such as infections. Loss of the Drosophila paralog Parg showed lethality in response to oxidative challenge that was rescued by human ADPRHL2, suggesting functional conservation. Pharmacological inhibition of PARP also rescued the phenotype, suggesting the possibility of postnatal treatment for this genetic condition.

Bi-allelic POLR3A Loss-of-Function Variants Cause Autosomal-Recessive Wiedemann-Rautenstrauch Syndrome. - Wambach, Jennifer A; Wegner, Daniel J; Patni, Nivedita; Kircher, Martin; Willing, Marcia C; Baldridge, Dustin; Xing, Chao; Agarwal, Anil K; Vergano, Samantha A Schrier; Patel, Chirag; Grange, Dorothy K; Kenney, Amy; et al. (Am J Hum Genet, 2018)
Wiedemann-Rautenstrauch syndrome (WRS), also known as neonatal progeroid syndrome, is a rare disorder of unknown etiology. It has been proposed to be autosomal-recessive and is characterized by variable clinical features, such as intrauterine growth restriction and poor postnatal weight gain, characteristic facial features (triangular appearance to the face, convex nasal profile or pinched nose, and small mouth), widened fontanelles, pseudohydrocephalus, prominent scalp veins, lipodystrophy, and teeth abnormalities. A previous report described a single WRS patient with bi-allelic truncating and splicing variants in POLR3A. Here we present seven additional infants, children, and adults with WRS and bi-allelic truncating and/or splicing variants in POLR3A. POLR3A, the largest subunit of RNA polymerase III, is a DNA-directed RNA polymerase that transcribes many small noncoding RNAs that regulate transcription, RNA processing, and translation. Bi-allelic missense variants in POLR3A have been associated with phenotypes distinct from WRS: hypogonadotropic hypogonadism and hypomyelinating leukodystrophy with or without oligodontia. Our findings confirm the association of bi-allelic POLR3A variants with WRS, expand the clinical phenotype of WRS, and suggest specific POLR3A genotypes associated with WRS and hypomyelinating leukodystrophy.

Biallelic variants in KIF14 cause intellectual disability with microcephaly. - Makrythanasis, Periklis; Maroofian, Reza; Stray-Pedersen, Asbjørg; Musaev, Damir; Zaki, Maha S; Mahmoud, Iman G; Selim, Laila; Elbadawy, Amera; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Gambin, Tomasz; Sorte, Hanne S; et al. (Eur J Hum Genet, 2018)
Kinesin proteins are critical for various cellular functions such as intracellular transport and cell division, and many members of the family have been linked to monogenic disorders and cancer. We report eight individuals with intellectual disability and microcephaly from four unrelated families with parental consanguinity. In the affected individuals of each family, homozygosity for likely pathogenic variants in KIF14 were detected; two loss-of-function (p.Asn83Ilefs*3 and p.Ser1478fs), and two missense substitutions (p.Ser841Phe and p.Gly459Arg). KIF14 is a mitotic motor protein that is required for spindle localization of the mitotic citron rho-interacting kinase, CIT, also mutated in microcephaly. Our results demonstrate the involvement of KIF14 in development and reveal a wide phenotypic variability ranging from fetal lethality to moderate developmental delay and microcephaly.
Keywords: Child; Child, Preschool; Female; Humans; Intellectual Disability; Kinesin; Loss of Function Mutation; Microcephaly; Mutation, Missense; Oncogene Proteins; Pedigree; Phenotype; Protein Domains; Syndrome

CARD14-associated papulosquamous eruption: A spectrum including features of psoriasis and pityriasis rubra pilaris. - Craiglow, Brittany G; Boyden, Lynn M; Hu, Ronghua; Virtanen, Marie; Su, John; Rodriguez, Gabriela; McCarthy, Catherine; Luna, Paula; Larralde, Margarita; Humphrey, Stephen; Holland, Kristen E; Hogeling, Marcia; et al. (J Am Acad Dermatol, 2018)
BACKGROUND: Heterozygous mutations in caspase recruitment domain family member 14 gene (CARD14) have been shown to be associated with psoriasis and familial pityriasis rubra pilaris (PRP). Many subjects with CARD14 mutations display features of both disorders, which can result in diagnostic uncertainty. In addition, these eruptions are often recalcitrant to conventional psoriasis therapies such as methotrexate, oral retinoids, and tumor necrosis factor-α inhibitors. OBJECTIVE: We sought to describe the clinical characteristics, family history, and response to therapy in subjects with papulosquamous eruptions due to mutations in CARD14. METHODS: Subjects were referred for genetic testing as part of a registry of subjects with inherited disorders of keratinization. DNA was isolated from blood or saliva, and multiplex targeted sequencing or whole exome sequencing was performed. Clinical histories of subjects with CARD14 mutations were reviewed. RESULTS: We identified 15 kindreds with CARD14-associated papulosquamous eruption (CAPE). Characteristic features of CAPE include early age of onset; prominent involvement of the cheeks, chin, and ears; family history of psoriasis or PRP; minimal response to conventional topical and systemic psoriasis therapies; and improvement with ustekinumab. LIMITATIONS: Relatively small sample size. CONCLUSIONS: Many subjects with CARD14 mutations display characteristics of both psoriasis and PRP. We propose the term CARD14-associated papulosquamous eruption to describe this spectrum of disease. Subjects with clinical features suggestive of CAPE should undergo CARD14 sequencing and may benefit from treatment with ustekinumab.
Keywords: Age of Onset; CARD Signaling Adaptor Proteins; Child; Child, Preschool; Dermatologic Agents; Facial Dermatoses; Genetic Testing; Guanylate Cyclase; Humans; Infant; Infant, Newborn; Membrane Proteins; Phenotype; Pityriasis Rubra Pilaris; Psoriasis; Retreatment; Skin Diseases, Papulosquamous; Ustekinumab

CLCN2 chloride channel mutations in familial hyperaldosteronism type II. - Scholl, Ute I; Stölting, Gabriel; Schewe, Julia; Thiel, Anne; Tan, Hua; Nelson-Williams, Carol; Vichot, Alfred A; Jin, Sheng Chih; Loring, Erin; Untiet, Verena; Yoo, Taekyeong; Choi, Jungmin; et al. (Nat Genet, 2018)
Primary aldosteronism, a common cause of severe hypertension , features constitutive production of the adrenal steroid aldosterone. We analyzed a multiplex family with familial hyperaldosteronism type II (FH-II) and 80 additional probands with unsolved early-onset primary aldosteronism. Eight probands had novel heterozygous variants in CLCN2, including two de novo mutations and four independent occurrences of a mutation encoding an identical p.Arg172Gln substitution; all relatives with early-onset primary aldosteronism carried the CLCN2 variant found in the proband. CLCN2 encodes a voltage-gated chloride channel expressed in adrenal glomerulosa that opens at hyperpolarized membrane potentials. Channel opening depolarizes glomerulosa cells and induces expression of aldosterone synthase, the rate-limiting enzyme for aldosterone biosynthesis. Mutant channels show gain of function, with higher open probabilities at the glomerulosa resting potential. These findings for the first time demonstrate a role of anion channels in glomerulosa membrane potential determination, aldosterone production and hypertension. They establish the cause of a substantial fraction of early-onset primary aldosteronism.

ClinGen advancing genomic data-sharing standards as a GA4GH driver project. - Dolman, Lena; Page, Angela; Babb, Lawrence; Freimuth, Robert R; Arachchi, Harindra; Bizon, Chris; Brush, Matthew; Fiume, Marc; Haendel, Melissa; Hansen, David P; Milosavljevic, Aleksandar; Patel, Ronak Y; et al. (Hum Mutat, 2018)
The Clinical Genome Resource (ClinGen)'s work to develop a knowledge base to support the understanding of genes and variants for use in precision medicine and research depends on robust, broadly applicable, and adaptable technical standards for sharing data and information. To forward this goal, ClinGen has joined with the Global Alliance for Genomics and Health (GA4GH) to support the development of open, freely-available technical standards and regulatory frameworks for secure and responsible sharing of genomic and health-related data. In its capacity as one of the 15 inaugural GA4GH "Driver Projects," ClinGen is providing input on the key standards needs of the global genomics community, and has committed to participate on GA4GH Work Streams to support the development of: (1) a standard model for computer-readable variant representation; (2) a data model for linking variant data to annotations; (3) a specification to enable sharing of genomic variant knowledge and associated clinical interpretations; and (4) a set of best practices for use of phenotype and disease ontologies. ClinGen's participation as a GA4GH Driver Project will provide a robust environment to test drive emerging genomic knowledge sharing standards and prove their utility among the community, while accelerating the construction of the ClinGen evidence base.

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease. - Liu, Jiaqi; Zhou, Yangzhong; Liu, Sen; Song, Xiaofei; Yang, Xin-Zhuang; Fan, Yanhui; Chen, Weisheng; Akdemir, Zeynep Coban; Yan, Zihui; Zuo, Yuzhi; Du, Renqian; Liu, Zhenlei; et al. (Hum Genet, 2018)
With the recent advance in genome-wide association studies (GWAS), disease-associated single nucleotide polymorphisms (SNPs) and copy number variants (CNVs) have been extensively reported. Accordingly, the issue of incorrect identification of recombination events that can induce the distortion of multi-allelic or hemizygous variants has received more attention. However, the potential distorted calculation bias or significance of a detected association in a GWAS due to the coexistence of CNVs and SNPs in the same genomic region may remain under-recognized. Here we performed the association study within a congenital scoliosis (CS) cohort whose genetic etiology was recently elucidated as a compound inheritance model, including mostly one rare variant deletion CNV null allele and one common variant non-coding hypomorphic haplotype of the TBX6 gene. We demonstrated that the existence of a deletion in TBX6 led to an overestimation of the contribution of the SNPs on the hypomorphic allele. Furthermore, we generalized a model to explain the calculation bias, or distorted significance calculation for an association study, that can be 'induced' by CNVs at a locus. Meanwhile, overlapping between the disease-associated SNPs from published GWAS and common CNVs (overlap 10%) and pathogenic/likely pathogenic CNVs (overlap 99.69%) was significantly higher than the random distribution (p < 1 × 10 and p = 0.034, respectively), indicating that such co-existence of CNV and SNV alleles might generally influence data interpretation and potential outcomes of a GWAS. We also verified and assessed the influence of colocalizing CNVs to the detection sensitivity of disease-associated SNP variant alleles in another adolescent idiopathic scoliosis (AIS) genome-wide association study. We proposed that detecting co-existent CNVs when evaluating the association signals between SNPs and disease traits could improve genetic model analyses and better integrate GWAS with robust Mendelian principles.
Keywords: Adolescent; Congenital Abnormalities; DNA Copy Number Variations; Female; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genomics; Genotype; Haplotypes; Humans; Phenotype; Polymorphism, Single Nucleotide; Scoliosis

Comparative genomic analysis of embryonic, lineage-converted and stem cell-derived motor neurons. - Ichida, Justin K; Staats, Kim A; Davis-Dusenbery, Brandi N; Clement, Kendell; Galloway, Kate E; Babos, Kimberly N; Shi, Yingxiao; Son, Esther Y; Kiskinis, Evangelos; Atwater, Nicholas; Gu, Hongcang; Gnirke, Andreas; et al. (Development, 2018)
Advances in stem cell science allow the production of different cell types either through the recapitulation of developmental processes, often termed 'directed differentiation', or the forced expression of lineage-specific transcription factors. Although cells produced by both approaches are increasingly used in translational applications, their quantitative similarity to their primary counterparts remains largely unresolved. To investigate the similarity between -derived and primary cell types, we harvested and purified mouse spinal motor neurons and compared them with motor neurons produced by transcription factor-mediated lineage conversion of fibroblasts or directed differentiation of pluripotent stem cells. To enable unbiased analysis of these motor neuron types and their cells of origin, we then subjected them to whole transcriptome and DNA methylome analysis by RNA sequencing (RNA-seq) and reduced representation bisulfite sequencing (RRBS). Despite major differences in methodology, lineage conversion and directed differentiation both produce cells that closely approximate the primary motor neuron state. However, we identify differences in Fas signaling, the Hox code and synaptic gene expression between lineage-converted and directed differentiation motor neurons that affect their utility in translational studies.
Keywords: Animals; Cell Lineage; Embryo, Mammalian; Epigenesis, Genetic; Genomics; Mice, Inbred C57BL; Motor Neurons; Pluripotent Stem Cells; Transcription, Genetic

A comprehensive clinical and genetic study in 127 patients with ID in Kinshasa, DR Congo. - Lumaka, Aimé; Race, Valerie; Peeters, Hilde; Corveleyn, Anniek; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Song, Xiaofei; Mubungu, Gerrye; Posey, Jennifer; Lupski, James R; Vermeesch, Joris R; Lukusa, Prosper; et al. (Am J Med Genet A, 2018)
Pathogenic variants account for 4 to 41% of patients with intellectual disability (ID) or developmental delay (DD). In Sub-Saharan Africa, the prevalence of ID is thought to be higher, but data in Central Africa are limited to some case reports. In addition, clinical descriptions of some syndromes are not available for this population. This study aimed at providing an estimate for the fraction of ID/DD for which an underlying etiological genetic cause may be elucidated and provide insights into their clinical presentation in special institutions in a Central African country. A total of 127 patients (33 females and 94 males, mean age 10.03 ± 4.68 years), were recruited from six institutions across Kinshasa. A clinical diagnosis was achieved in 44 but molecular confirmation was achieved in 21 of the 22 patients with expected genetic defect (95% clinical sensitivity). Identified diseases included Down syndrome (15%), submicroscopic copy number variants (9%), aminoacylase deficiency (0.8%), Partington syndrome in one patient (0.8%) and his similarly affected brother, X-linked syndromic Mental Retardation type 33 (0.8%), and two conditions without clear underlying molecular genetic etiologies (Oculo-Auriculo-Vertebral and Amniotic Bands Sequence). We have shown that genetic etiologies, similar to those reported in Caucasian subjects, are a common etiologic cause of ID in African patients from Africa. We have confirmed the diagnostic utility of clinical characterization prior to genetic testing. Finally, our clinical descriptions provide insights into the presentation of these genetic diseases in African patients.

Comprehensive genomic analysis of patients with disorders of cerebral cortical development. - Wiszniewski, Wojciech; Gawlinski, Pawel; Gambin, Tomasz; Bekiesinska-Figatowska, Monika; Obersztyn, Ewa; Antczak-Marach, Dorota; Akdemir, Zeynep Hande Coban; Harel, Tamar; Karaca, Ender; Jurek, Marta; Sobecka, Katarzyna; Nowakowska, Beata; et al. (Eur J Hum Genet, 2018)
Malformations of cortical development (MCDs) manifest with structural brain anomalies that lead to neurologic sequelae, including epilepsy, cerebral palsy, developmental delay, and intellectual disability. To investigate the underlying genetic architecture of patients with disorders of cerebral cortical development, a cohort of 54 patients demonstrating neuroradiologic signs of MCDs was investigated. Individual genomes were interrogated for single-nucleotide variants (SNV) and copy number variants (CNV) with whole-exome sequencing and chromosomal microarray studies. Variation affecting known MCDs-associated genes was found in 16/54 cases, including 11 patients with SNV, 2 patients with CNV, and 3 patients with both CNV and SNV, at distinct loci. Diagnostic pathogenic SNV and potentially damaging variants of unknown significance (VUS) were identified in two groups of seven individuals each. We demonstrated that de novo variants are important among patients with MCDs as they were identified in 10/16 individuals with a molecular diagnosis. Three patients showed changes in known MCDs genes  and a clinical phenotype beyond the usual characteristics observed, i.e., phenotypic expansion, for a particular known disease gene clinical entity. We also discovered 2 likely candidate genes, CDH4, and ASTN1, with human and animal studies supporting their roles in brain development, and 5 potential candidate genes. Our findings emphasize genetic heterogeneity of MCDs disorders and postulate potential novel candidate genes involved in cerebral cortical development.
Keywords: Cadherins; DNA Copy Number Variations; Exome; Female; Genetic Heterogeneity; Humans; Male; Malformations of Cortical Development; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Cell Surface

Confirmation of the Role of DHX38 in the Etiology of Early-Onset Retinitis Pigmentosa. - Latif, Zahid; Chakchouk, Imen; Schrauwen, Isabelle; Lee, Kwanghyuk; Santos-Cortez, Regie Lyn P; Abbe, Izoduwa; Acharya, Anushree; Jarral, Afeefa; Ali, Imran; Ullah, Ehsan; Khan, Muhammad Nasim; Ali, Ghazanfar; et al. (Invest Ophthalmol Vis Sci, 2018)
Purpose: Retinitis pigmentosa (RP) is a genetically heterogeneous trait with autosomal-recessive (ar) inheritance underlying 50% of genetic disease cases. Sixty-one arRP genes have been identified, and recently, DHX38 has been reported as a potential candidate gene for arRP with only a single family reported with a variant of unknown significance. We identified a missense variant in DHX38 that co-segregates with the arRP phenotype in two Pakistani families confirming the involvement of DHX38 in the etiology of early-onset RP. Methods: Exome sequencing was performed using two DNA samples from affected members of Pakistani families (MA88 and MA157) with early onset arRP. Sanger sequencing of DNA samples from all family members confirmed the segregation of candidate variant within both families. Results: A novel missense DHX38 variant c.971G>A; p.(Arg324Gln) was identified which segregates with the arRP phenotype and yielded a logarithm of the odds (LOD) score of 5.0 and 4.3 for families MA88 and MA157, respectively. This variant is predicted to be conserved and deleterious by several bioinformatics tools. Conclusions: We identified a second deleterious DHX38 variant that segregates with arRP in two families, providing additional evidence that DHX38 is involved in RP etiology. DHX38 encodes for pre-mRNA splicing factor PRP16, which is important in catalyzing pre-mRNA splicing.
Keywords: Adolescent; Adult; Cataract; Computational Biology; DEAD-box RNA Helicases; Female; Genes, Recessive; Genetic Association Studies; Genetic Linkage; Humans; Male; Mutation, Missense; Nucleotide Mapping; Ophthalmoscopy; Pedigree; Retinitis Pigmentosa; RNA Splicing Factors; Sequence Analysis, DNA; Whole Exome Sequencing; Young Adult

The Congenital Heart Disease Genetic Network Study: Cohort description. - Hoang, Thanh T; Goldmuntz, Elizabeth; Roberts, Amy E; Chung, Wendy K; Kline, Jennie K; Deanfield, John E; Giardini, Alessandro; Aleman, Adolfo; Gelb, Bruce D; Mac Neal, Meghan; Porter, George A; Kim, Richard; et al. (PLoS One, 2018)
The Pediatric Cardiac Genomics Consortium (PCGC) designed the Congenital Heart Disease Genetic Network Study to provide phenotype and genotype data for a large congenital heart defects (CHDs) cohort. This article describes the PCGC cohort, overall and by major types of CHDs (e.g., conotruncal defects) and subtypes of conotrucal heart defects (e.g., tetralogy of Fallot) and left ventricular outflow tract obstructions (e.g., hypoplastic left heart syndrome). Cases with CHDs were recruited through ten sites, 2010-2014. Information on cases (N = 9,727) and their parents was collected through interviews and medical record abstraction. Four case characteristics, eleven parental characteristics, and thirteen parent-reported neurodevelopment outcomes were summarized using counts and frequencies and compared across CHD types and subtypes. Eleven percent of cases had a genetic diagnosis. Among cases without a genetic diagnosis, the majority had conotruncal heart defects (40%) or left ventricular outflow tract obstruction (21%). Across CHD types, there were significant differences (p<0.05) in the distribution of all four case characteristics (e.g., sex), four parental characteristics (e.g., maternal pregestational diabetes), and five neurodevelopmental outcomes (e.g., learning disabilities). Several characteristics (e.g., sex) were also significantly different across CHD subtypes. The PCGC cohort is one of the largest CHD cohorts available for the study of genetic determinants of risk and outcomes. The majority of cases do not have a genetic diagnosis. This description of the PCGC cohort, including differences across CHD types and subtypes, provides a reference work for investigators who are interested in collaborating with or using publically available resources from the PCGC.
Keywords: Adult; Cohort Studies; Female; Gene Regulatory Networks; Heart Defects, Congenital; Humans; Male; Phenotype

Congenital Titinopathy: Comprehensive characterization and pathogenic insights. - Oates, Emily C; Jones, Kristi J; Donkervoort, Sandra; Charlton, Amanda; Brammah, Susan; Smith, John E; Ware, James S; Yau, Kyle S; Swanson, Lindsay C; Whiffin, Nicola; Peduto, Anthony J; Bournazos, Adam; et al. (Ann Neurol, 2018)
OBJECTIVE: Comprehensive clinical characterization of congenital titinopathy to facilitate diagnosis and management of this important emerging disorder. METHODS: Using massively parallel sequencing we identified 30 patients from 27 families with 2 pathogenic nonsense, frameshift and/or splice site TTN mutations in trans. We then undertook a detailed analysis of the clinical, histopathological and imaging features of these patients. RESULTS: All patients had prenatal or early onset hypotonia and/or congenital contractures. None had ophthalmoplegia. Scoliosis and respiratory insufficiency typically developed early and progressed rapidly, whereas limb weakness was often slowly progressive, and usually did not prevent independent walking. Cardiac involvement was present in 46% of patients. Relatives of 2 patients had dilated cardiomyopathy. Creatine kinase levels were normal to moderately elevated. Increased fiber size variation, internalized nuclei and cores were common histopathological abnormalities. Cap-like regions, whorled or ring fibers, and mitochondrial accumulations were also observed. Muscle magnetic resonance imaging showed gluteal, hamstring and calf muscle involvement. Western blot analysis showed a near-normal sized titin protein in all samples. The presence of 2 mutations predicted to impact both N2BA and N2B cardiac isoforms appeared to be associated with greatest risk of cardiac involvement. One-third of patients had 1 mutation predicted to impact exons present in fetal skeletal muscle, but not included within the mature skeletal muscle isoform transcript. This strongly suggests developmental isoforms are involved in the pathogenesis of this congenital/early onset disorder. INTERPRETATION: This detailed clinical reference dataset will greatly facilitate diagnostic confirmation and management of patients, and has provided important insights into disease pathogenesis. Ann Neurol 2018;83:1105-1124.

Co-occurrence of frameshift mutations in and in a child with complex craniosynostosis. - Timberlake, Andrew T; Wu, Robin; Nelson-Williams, Carol; Furey, Charuta G; Hildebrand, Kristi I; Elton, Scott W; Wood, Jeyhan S; Persing, John A; Lifton, Richard P (Hum Genome Var, 2018)
Non-syndromic craniosynostosis (CS) affects 1 in 2350 live births. Recent studies have shown that a significant fraction of cases are caused by de novo or rare transmitted mutations that promote premature osteoblast differentiation in cranial sutures. Rare heterozygous loss-of-function (LOF) mutations in and are highly enriched in patients with non-syndromic sagittal and coronal CS, respectively. Interestingly, both mutations show striking incomplete penetrance, suggesting a role for modifying alleles; in the case of , a common variant near drastically increases penetrance of sagittal CS. Here, we report a proband presenting with both sagittal and coronal craniosynostosis with the highly unusual recurrence of CS within two months of initial surgery, requiring a second operation to re-establish suture patency at six months of age. Exome sequencing revealed a rare transmitted frameshift mutation in (p. 152 fs*27) inherited from an unaffected parent, absence of the common risk variant, and a de novo frameshift mutation in (p.E548fs*14). and independently inhibit transcriptional targets of BMP signaling. The findings are consistent with epistasis of these mutations, increasing penetrance and severity of CS in this proband. They also add to the list of composite phenotypes resulting from two Mendelian mutations, and support the utility of exome sequencing in atypical CS cases.

De Novo Sequence and Copy Number Variants Are Strongly Associated with Tourette Disorder and Implicate Cell Polarity in Pathogenesis. - Wang, Sheng; Mandell, Jeffrey D; Kumar, Yogesh; Sun, Nawei; Morris, Montana T; Arbelaez, Juan; Nasello, Cara; Dong, Shan; Duhn, Clif; Zhao, Xin; Yang, Zhiyu; Padmanabhuni, Shanmukha S; et al. (Cell Rep, 2018)
We previously established the contribution of de novo damaging sequence variants to Tourette disorder (TD) through whole-exome sequencing of 511 trios. Here, we sequence an additional 291 TD trios and analyze the combined set of 802 trios. We observe an overrepresentation of de novo damaging variants in simplex, but not multiplex, families; we identify a high-confidence TD risk gene, CELSR3 (cadherin EGF LAG seven-pass G-type receptor 3); we find that the genes mutated in TD patients are enriched for those related to cell polarity, suggesting a common pathway underlying pathobiology; and we confirm a statistically significant excess of de novo copy number variants in TD. Finally, we identify significant overlap of de novo sequence variants between TD and obsessive-compulsive disorder and de novo copy number variants between TD and autism spectrum disorder, consistent with shared genetic risk.

De novo variants in congenital diaphragmatic hernia identify MYRF as a new syndrome and reveal genetic overlaps with other developmental disorders. - Qi, Hongjian; Yu, Lan; Zhou, Xueya; Wynn, Julia; Zhao, Haoquan; Guo, Yicheng; Zhu, Na; Kitaygorodsky, Alexander; Hernan, Rebecca; Aspelund, Gudrun; Lim, Foong-Yen; Crombleholme, Timothy; et al. (PLoS Genet, 2018)
Congenital diaphragmatic hernia (CDH) is a severe birth defect that is often accompanied by other congenital anomalies. Previous exome sequencing studies for CDH have supported a role of de novo damaging variants but did not identify any recurrently mutated genes. To investigate further the genetics of CDH, we analyzed de novo coding variants in 362 proband-parent trios including 271 new trios reported in this study. We identified four unrelated individuals with damaging de novo variants in MYRF (P = 5.3x10(-8)), including one likely gene-disrupting (LGD) and three deleterious missense (D-mis) variants. Eight additional individuals with de novo LGD or missense variants were identified from our other genetic studies or from the literature. Common phenotypes of MYRF de novo variant carriers include CDH, congenital heart disease and genitourinary abnormalities, suggesting that it represents a novel syndrome. MYRF is a membrane associated transcriptional factor highly expressed in developing diaphragm and is depleted of LGD variants in the general population. All de novo missense variants aggregated in two functional protein domains. Analyzing the transcriptome of patient-derived diaphragm fibroblast cells suggest that disease associated variants abolish the transcription factor activity. Furthermore, we showed that the remaining genes with damaging variants in CDH significantly overlap with genes implicated in other developmental disorders. Gene expression patterns and patient phenotypes support pleiotropic effects of damaging variants in these genes on CDH and other developmental disorders. Finally, functional enrichment analysis implicates the disruption of regulation of gene expression, kinase activities, intra-cellular signaling, and cytoskeleton organization as pathogenic mechanisms in CDH.
Keywords: Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Female; Genetic Variation; Heart Defects, Congenital; Hernias, Diaphragmatic, Congenital; Humans; Infant, Newborn; Longitudinal Studies; Male; Membrane Proteins; Mutation; Mutation, Missense; Phenotype; Sequence Analysis, RNA; Syndrome; Transcription Factors; Whole Exome Sequencing; Whole Genome Sequencing

De Novo Variants in the F-Box Protein FBXO11 in 20 Individuals with a Variable Neurodevelopmental Disorder. - Gregor, Anne; Sadleir, Lynette G; Asadollahi, Reza; Azzarello-Burri, Silvia; Battaglia, Agatino; Ousager, Lilian Bomme; Boonsawat, Paranchai; Bruel, Ange-Line; Buchert, Rebecca; Calpena, Eduardo; Cogné, Benjamin; Dallapiccola, Bruno; et al. (Am J Hum Genet, 2018)
Next-generation sequencing combined with international data sharing has enormously facilitated identification of new disease-associated genes and mutations. This is particularly true for genetically extremely heterogeneous entities such as neurodevelopmental disorders (NDDs). Through exome sequencing and world-wide collaborations, we identified and assembled 20 individuals with de novo variants in FBXO11. They present with mild to severe developmental delay associated with a range of features including short (4/20) or tall (2/20) stature, obesity (5/20), microcephaly (4/19) or macrocephaly (2/19), behavioral problems (17/20), seizures (5/20), cleft lip or palate or bifid uvula (3/20), and minor skeletal anomalies. FBXO11 encodes a member of the F-Box protein family, constituting a subunit of an E3-ubiquitin ligase complex. This complex is involved in ubiquitination and proteasomal degradation and thus in controlling critical biological processes by regulating protein turnover. The identified de novo aberrations comprise two large deletions, ten likely gene disrupting variants, and eight missense variants distributed throughout FBXO11. Structural modeling for missense variants located in the CASH or the Zinc-finger UBR domains suggests destabilization of the protein. This, in combination with the observed spectrum and localization of identified variants and the lack of apparent genotype-phenotype correlations, is compatible with loss of function or haploinsufficiency as an underlying mechanism. We implicate de novo missense and likely gene disrupting variants in FBXO11 in a neurodevelopmental disorder with variable intellectual disability and various other features.

Detection of variants in dystroglycanopathy-associated genes through the application of targeted whole-exome sequencing analysis to a large cohort of patients with unexplained limb-girdle muscle weakness. - Johnson, Katherine; Bertoli, Marta; Phillips, Lauren; Topf, Ana; Van den Bergh, Peter; Vissing, John; Witting, Nanna; Nafissi, Shahriar; Jamal-Omidi, Shirin; Łusakowska, Anna; Kostera-Pruszczyk, Anna; Potulska-Chromik, Anna; et al. (Skelet Muscle, 2018)
BACKGROUND: Dystroglycanopathies are a clinically and genetically heterogeneous group of disorders that are typically characterised by limb-girdle muscle weakness. Mutations in 18 different genes have been associated with dystroglycanopathies, the encoded proteins of which typically modulate the binding of α-dystroglycan to extracellular matrix ligands by altering its glycosylation. This results in a disruption of the structural integrity of the myocyte, ultimately leading to muscle degeneration. METHODS: Deep phenotypic information was gathered using the PhenoTips online software for 1001 patients with unexplained limb-girdle muscle weakness from 43 different centres across 21 European and Middle Eastern countries. Whole-exome sequencing with at least 250 ng DNA was completed using an Illumina exome capture and a 38 Mb baited target. Genes known to be associated with dystroglycanopathies were analysed for disease-causing variants. RESULTS: Suspected pathogenic variants were detected in DPM3, ISPD, POMT1 and FKTN in one patient each, in POMK in two patients, in GMPPB in three patients, in FKRP in eight patients and in POMT2 in ten patients. This indicated a frequency of 2.7% for the disease group within the cohort of 1001 patients with unexplained limb-girdle muscle weakness. The phenotypes of the 27 patients were highly variable, yet with a fundamental presentation of proximal muscle weakness and elevated serum creatine kinase. CONCLUSIONS: Overall, we have identified 27 patients with suspected pathogenic variants in dystroglycanopathy-associated genes. We present evidence for the genetic and phenotypic diversity of the dystroglycanopathies as a disease group, while also highlighting the advantage of incorporating next-generation sequencing into the diagnostic pathway of rare diseases.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Child; Child, Preschool; Dystroglycans; Female; Genetic Predisposition to Disease; Genetic Variation; Glycosylation; Heterozygote; Homozygote; Humans; Male; Middle Aged; Muscle Proteins; Muscular Dystrophies, Limb-Girdle; Mutation; Phenotype; Whole Exome Sequencing; Young Adult

Discordance in the Dependence on Kisspeptin Signaling in Mini Puberty vs Adolescent Puberty: Human Genetic Evidence. - Shahab, Muhammad; Lippincott, Margaret; Chan, Yee-Ming; Davies, Addie; Merino, Paulina M; Plummer, Lacey; Mericq, Veronica; Seminara, Stephanie (J Clin Endocrinol Metab, 2018)
Context: Hypothalamic kisspeptin signaling plays a critical role in the initiation and maintenance of reproductive function. Biallelic mutations in the coding sequence of KISS1R (GPR54) have been identified in patients with idiopathic hypogonadotropic hypogonadism, but it is unknown whether biallelic variants can also be associated with related reproductive disorders. Case Description: A missense homozygous variant (c.890G>T p.R297L) in KISS1R was identified in a child who presented with microphallus and bilateral cryptorchidism. This variant has been reported to reduce, but not abolish, postreceptor signaling in vitro. Biochemical evaluation during the neonatal period revealed low testosterone levels. By 11 years and 8 months, the boy began demonstrating increases in testicular volume. By 17 years and 3 months, his testicular volume was 20 mL; his penile length was 7.3 cm; and he had adult levels of circulating gonadotropins and testosterone. Conclusion: This case report associates biallelic loss-of-function mutations in KISS1R with normal timing of adolescent puberty. Because these coding sequence variants occurred in a patient with microphallus and cryptorchidism, they demonstrate different levels of dependence of the hypothalamic-pituitary-gonadal cascade on kisspeptin signaling at distinct times in the reproductive life span. The suppression of the hypothalamic-pituitary-gonadal cascade during early life but not adolescence suggests that the mini puberty of infancy depends more on kisspeptin-induced, gonadotropin-releasing hormone-induced luteinizing hormone secretion than does adolescent puberty.
Keywords: Cryptorchidism; Follicle Stimulating Hormone; Follow-Up Studies; Humans; Infant; Kisspeptins; Luteinizing Hormone; Male; Mutation, Missense; Penis; Receptors, Kisspeptin-1; Sexual Maturation; Signal Transduction; Testosterone

Dissecting the Causal Mechanism of X-Linked Dystonia-Parkinsonism by Integrating Genome and Transcriptome Assembly. - Aneichyk, Tatsiana; Hendriks, William T; Yadav, Rachita; Shin, David; Gao, Dadi; Vaine, Christine A; Collins, Ryan L; Domingo, Aloysius; Currall, Benjamin; Stortchevoi, Alexei; Multhaupt-Buell, Trisha; Penney, Ellen B; et al. (Cell, 2018)
X-linked Dystonia-Parkinsonism (XDP) is a Mendelian neurodegenerative disease that is endemic to the Philippines and is associated with a founder haplotype. We integrated multiple genome and transcriptome assembly technologies to narrow the causal mutation to the TAF1 locus, which included a SINE-VNTR-Alu (SVA) retrotransposition into intron 32 of the gene. Transcriptome analyses identified decreased expression of the canonical cTAF1 transcript among XDP probands, and de novo assembly across multiple pluripotent stem-cell-derived neuronal lineages discovered aberrant TAF1 transcription that involved alternative splicing and intron retention (IR) in proximity to the SVA that was anti-correlated with overall TAF1 expression. CRISPR/Cas9 excision of the SVA rescued this XDP-specific transcriptional signature and normalized TAF1 expression in probands. These data suggest an SVA-mediated aberrant transcriptional mechanism associated with XDP and may provide a roadmap for layered technologies and integrated assembly-based analyses for other unsolved Mendelian disorders.
Keywords: Alternative Splicing; Alu Elements; Base Sequence; Cohort Studies; CRISPR-Cas Systems; Dystonic Disorders; Family; Female; Genetic Diseases, X-Linked; Genetic Loci; Genome, Human; Haplotypes; High-Throughput Nucleotide Sequencing; Histone Acetyltransferases; Humans; Induced Pluripotent Stem Cells; Introns; Male; Minisatellite Repeats; Models, Genetic; Nerve Degeneration; Neural Stem Cells; Neurons; RNA, Messenger; Short Interspersed Nucleotide Elements; TATA-Binding Protein Associated Factors; Transcription Factor TFIID; Transcriptome

Dual Molecular Effects of Dominant RORA Mutations Cause Two Variants of Syndromic Intellectual Disability with Either Autism or Cerebellar Ataxia. - Guissart, Claire; Latypova, Xénia; Rollier, Paul; Khan, Tahir N; Stamberger, Hannah; McWalter, Kirsty; Cho, Megan T; Kjaergaard, Susanne; Weckhuysen, Sarah; Lesca, Gaetan; Besnard, Thomas; Õunap, Katrin; et al. (Am J Hum Genet, 2018)
RORα, the RAR-related orphan nuclear receptor alpha, is essential for cerebellar development. The spontaneous mutant mouse staggerer, with an ataxic gait caused by neurodegeneration of cerebellar Purkinje cells, was discovered two decades ago to result from homozygous intragenic Rora deletions. However, RORA mutations were hitherto undocumented in humans. Through a multi-centric collaboration, we identified three copy-number variant deletions (two de novo and one dominantly inherited in three generations), one de novo disrupting duplication, and nine de novo point mutations (three truncating, one canonical splice site, and five missense mutations) involving RORA in 16 individuals from 13 families with variable neurodevelopmental delay and intellectual disability (ID)-associated autistic features, cerebellar ataxia, and epilepsy. Consistent with the human and mouse data, disruption of the D. rerio ortholog, roraa, causes significant reduction in the size of the developing cerebellum. Systematic in vivo complementation studies showed that, whereas wild-type human RORA mRNA could complement the cerebellar pathology, missense variants had two distinct pathogenic mechanisms of either haploinsufficiency or a dominant toxic effect according to their localization in the ligand-binding or DNA-binding domains, respectively. This dichotomous direction of effect is likely relevant to the phenotype in humans: individuals with loss-of-function variants leading to haploinsufficiency show ID with autistic features, while individuals with de novo dominant toxic variants present with ID, ataxia, and cerebellar atrophy. Our combined genetic and functional data highlight the complex mutational landscape at the human RORA locus and suggest that dual mutational effects likely determine phenotypic outcome.
Keywords: Adolescent; Adult; Aged, 80 and over; Alleles; Animals; Autistic Disorder; Brain; Cerebellar Ataxia; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Female; Genes, Dominant; Genetic Complementation Test; Humans; Intellectual Disability; Larva; Magnetic Resonance Imaging; Male; Middle Aged; Mutation, Missense; Nuclear Receptor Subfamily 1, Group F, Member 1; Purkinje Cells; Syndrome; Zebrafish

Enrolling Genomics Research Participants through a Clinical Setting: the Impact of Existing Clinical Relationships on Informed Consent and Expectations for Return of Research Results. - Berrios, Courtney; James, Cynthia A; Raraigh, Karen; Bollinger, Juli; Murray, Brittney; Tichnell, Crystal; Applegate, Carolyn D; Bergner, Amanda L (J Genet Couns, 2018)
Genetic counselors working in a clinical setting may find themselves recruiting, enrolling, and returning results for genomic research, and existing clinical relationships with study participants may impact these research interactions. We present a qualitative study using semi-structured interviews of participants enrolled in a genome sequencing/exome sequencing (GS/ES) study at the same institution where they receive clinical care. Interviews were coded for motivations to participate and expectations of this research. The interviews revealed common motivations for participation, including altruism and hope for benefit for themselves, family members, and/or others with their condition. Additionally, themes emerged related to unintentional influence based on trust of the clinical provider that recruited them to the study. Participant trust in the enrolling provider at times appeared to extend to the study team to decide which research results to return and to do so in an appropriate format. Participants also based expectations for research results return on previous clinical genetic testing experiences, which may or may not be realistic depending on study design. It is imperative that genetic counselors enrolling patients into research studies be aware of the potential influence of their clinical relationship on potential subjects, be transparent about their role on the study team, and help set expectations about the study process, including results return.
Keywords: Base Sequence; Decision Making; Family; Female; Genetic Testing; Humans; Informed Consent; Male; Motivation; Qualitative Research; Research Design; Trust

ERCC4 variants identified in a cohort of patients with segmental progeroid syndromes. - Mori, Takayasu; Yousefzadeh, Matthew J; Faridounnia, Maryam; Chong, Jessica X; Hisama, Fuki M; Hudgins, Louanne; Mercado, Gabriela; Wade, Erin A; Barghouthy, Amira S; Lee, Lin; Martin, George M; Nickerson, Deborah A; et al. (Hum Mutat, 2018)
Pathogenic variants in genes, which encode DNA repair and damage response proteins, result in a number of genomic instability syndromes with features of accelerated aging. ERCC4 (XPF) encodes a protein that forms a complex with ERCC1 and is required for the 5' incision during nucleotide excision repair. ERCC4 is also FANCQ, illustrating a critical role in interstrand crosslink repair. Pathogenic variants in this gene cause xeroderma pigmentosum, XFE progeroid syndrome, Cockayne syndrome (CS), and Fanconi anemia. We performed massive parallel sequencing for 42 unsolved cases submitted to the International Registry of Werner Syndrome. Two cases, each carrying two novel heterozygous ERCC4 variants, were identified. The first case was a compound heterozygote for: c.2395C > T (p.Arg799Trp) and c.388+1164_792+795del (p.Gly130Aspfs*18). Further molecular and cellular studies indicated that the ERCC4 variants in this patient are responsible for a phenotype consistent with a variant of CS. The second case was heterozygous for two variants in cis: c.[1488A > T; c.2579C > A] (p.[Gln496His; Ala860Asp]). While the second case also had several phenotypic features of accelerated aging, we were unable to provide biological evidence supporting the pathogenic roles of the associated ERCC4 variants. Precise genetic causes and disease mechanism of the second case remains to be determined.
Keywords: Actins; Aged; Cockayne Syndrome; DNA Repair; DNA-Binding Proteins; Fanconi Anemia; Female; Genetic Predisposition to Disease; Humans; Lamin Type A; Male; Middle Aged; Pedigree; Xeroderma Pigmentosum

Expanding the genetic architecture and phenotypic spectrum in the skeletal ciliopathies. - Zhang, Wenjuan; Taylor, S Paige; Ennis, Hayley A; Forlenza, Kimberly N; Duran, Ivan; Li, Bing; Sanchez, Jorge A Ortiz; Nevarez, Lisette; Nickerson, Deborah A; Bamshad, Michael; Lachman, Ralph S; Krakow, Deborah; et al. (Hum Mutat, 2018)
Defects in the biosynthesis and/or function of primary cilia cause a spectrum of disorders collectively referred to as ciliopathies. A subset of these disorders is distinguished by profound abnormalities of the skeleton that include a long narrow chest with markedly short ribs, extremely short limbs, and polydactyly. These include the perinatal lethal short-rib polydactyly syndromes (SRPS) and the less severe asphyxiating thoracic dystrophy (ATD), Ellis-van Creveld (EVC) syndrome, and cranioectodermal dysplasia (CED) phenotypes. To identify new genes and define the spectrum of mutations in the skeletal ciliopathies, we analyzed 152 unrelated families with SRPS, ATD, and EVC. Causal variants were discovered in 14 genes in 120 families, including one newly associated gene and two genes previously associated with other ciliopathies. These three genes encode components of three different ciliary complexes; FUZ, which encodes a planar cell polarity complex molecule; TRAF3IP1, which encodes an anterograde ciliary transport protein; and LBR, which encodes a nuclear membrane protein with sterol reductase activity. The results established the molecular basis of SRPS type IV, in which mutations were identified in four different ciliary genes. The data provide systematic insight regarding the genotypes associated with a large cohort of these genetically heterogeneous phenotypes and identified new ciliary components required for normal skeletal development.
Keywords: Ciliopathies; Cytoplasmic Dyneins; Genetic Association Studies; Genetic Markers; Genetic Variation; Genotype; Humans; Mutation; Phenotype; Proteins; Radiography; Skeleton; Whole Exome Sequencing

FOXP3 mutations causing early-onset insulin-requiring diabetes but without other features of immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome. - Hwang, Jessica L; Park, Soo-Young; Ye, Honggang; Sanyoura, May; Pastore, Ashley N; Carmody, David; Del Gaudio, Daniela; Wilson, Janna F; Hanis, Craig L; Liu, Xiaoming; Atzmon, Gil; Glaser, Benjamin; et al. (Pediatr Diabetes, 2018)
Diabetes occurs in 1/90 000 to 1/160 000 births and when diagnosed under 6 months of age is very likely to have a primary genetic cause. FOXP3 encodes a transcription factor critical for T regulatory cell function and mutations are known to cause "immune dysregulation, polyendocrinopathy (including insulin-requiring diabetes), enteropathy, X-linked" (IPEX) syndrome. This condition is often fatal unless patients receive a bone-marrow transplant. Here we describe the phenotype of male neonates and infants who had insulin-requiring diabetes without other features of IPEX syndrome and were found to have mutations in FOXP3. Whole-exome or next generation sequencing of genes of interest was carried out in subjects with isolated neonatal diabetes without a known genetic cause. RT-PCR was carried out to investigate the effects on RNA splicing of a novel intronic splice-site variant. Four male subjects were found to have FOXP3 variants in the hemizygous state: p.Arg114Trp, p.Arg347His, p.Lys393Met, and c.1044+5G>A which was detected in 2 unrelated probands and in a brother diagnosed with diabetes at 2.1 years of age. Of these, p.Arg114Trp is likely a benign rare variant found in individuals of Ashkenazi Jewish ancestry and p.Arg347His has been previously described in patients with classic IPEX syndrome. The p.Lys393Met and c.1044+5G>A variants are novel to this study. RT-PCR studies of the c.1044+5G>A splice variant confirmed it affected RNA splicing by generating both a wild type and truncated transcript. We conclude that FOXP3 mutations can cause early-onset insulin-requiring diabetes with or without other features of IPEX syndrome.
Keywords: Diabetes Mellitus; Diabetes Mellitus, Type 1; Diarrhea; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immune System Diseases; Infant; Infant, Newborn; Male; Registries

Functional Dysregulation of CDC42 Causes Diverse Developmental Phenotypes. - Martinelli, Simone; Krumbach, Oliver H F; Pantaleoni, Francesca; Coppola, Simona; Amin, Ehsan; Pannone, Luca; Nouri, Kazem; Farina, Luciapia; Dvorsky, Radovan; Lepri, Francesca; Buchholzer, Marcel; Konopatzki, Raphael; et al. (Am J Hum Genet, 2018)
Exome sequencing has markedly enhanced the discovery of genes implicated in Mendelian disorders, particularly for individuals in whom a known clinical entity could not be assigned. This has led to the recognition that phenotypic heterogeneity resulting from allelic mutations occurs more commonly than previously appreciated. Here, we report that missense variants in CDC42, a gene encoding a small GTPase functioning as an intracellular signaling node, underlie a clinically heterogeneous group of phenotypes characterized by variable growth dysregulation, facial dysmorphism, and neurodevelopmental, immunological, and hematological anomalies, including a phenotype resembling Noonan syndrome, a developmental disorder caused by dysregulated RAS signaling. In silico, in vitro, and in vivo analyses demonstrate that mutations variably perturb CDC42 function by altering the switch between the active and inactive states of the GTPase and/or affecting CDC42 interaction with effectors, and differentially disturb cellular and developmental processes. These findings reveal the remarkably variable impact that dominantly acting CDC42 mutations have on cell function and development, creating challenges in syndrome definition, and exemplify the importance of functional profiling for syndrome recognition and delineation.

FUT2 Variants Confer Susceptibility to Familial Otitis Media. - Santos-Cortez, Regie Lyn P; Chiong, Charlotte M; Frank, Daniel N; Ryan, Allen F; Giese, Arnaud P J; Bootpetch Roberts, Tori; Daly, Kathleen A; Steritz, Matthew J; Szeremeta, Wasyl; Pedro, Melquiadesa; Pine, Harold; Yarza, Talitha Karisse L; et al. (Am J Hum Genet, 2018)
Non-secretor status due to homozygosity for the common FUT2 variant c.461G>A (p.Trp154) is associated with either risk for autoimmune diseases or protection against viral diarrhea and HIV. We determined the role of FUT2 in otitis media susceptibility by obtaining DNA samples from 609 multi-ethnic families and simplex case subjects with otitis media. Exome and Sanger sequencing, linkage analysis, and Fisher exact and transmission disequilibrium tests (TDT) were performed. The common FUT2 c.604C>T (p.Arg202) variant co-segregates with otitis media in a Filipino pedigree (LOD = 4.0). Additionally, a rare variant, c.412C>T (p.Arg138Cys), is associated with recurrent/chronic otitis media in European-American children (p = 1.2 × 10) and US trios (TDT p = 0.01). The c.461G>A (p.Trp154) variant was also over-transmitted in US trios (TDT p = 0.01) and was associated with shifts in middle ear microbiota composition (PERMANOVA p < 10) and increased biodiversity. When all missense and nonsense variants identified in multi-ethnic US trios with CADD > 20 were combined, FUT2 variants were over-transmitted in trios (TDT p = 0.001). Fut2 is transiently upregulated in mouse middle ear after inoculation with non-typeable Haemophilus influenzae. Four FUT2 variants-namely p.Ala104Val, p.Arg138Cys, p.Trp154, and p.Arg202-reduced A antigen in mutant-transfected COS-7 cells, while the nonsense variants also reduced FUT2 protein levels. Common and rare FUT2 variants confer susceptibility to otitis media, likely by modifying the middle ear microbiome through regulation of A antigen levels in epithelial cells. Our families demonstrate marked intra-familial genetic heterogeneity, suggesting that multiple combinations of common and rare variants plus environmental factors influence the individual otitis media phenotype as a complex trait.

Genetic analysis of CHARGE syndrome identifies overlapping molecular biology. - Moccia, Amanda; Srivastava, Anshika; Skidmore, Jennifer M; Bernat, John A; Wheeler, Marsha; Chong, Jessica X; Nickerson, Deborah; Bamshad, Michael; Hefner, Margaret A; Martin, Donna M; Bielas, Stephanie L (Genet Med, 2018)
PURPOSE: CHARGE syndrome is an autosomal-dominant, multiple congenital anomaly condition characterized by vision and hearing loss, congenital heart disease, and malformations of craniofacial and other structures. Pathogenic variants in CHD7, encoding adenosine triphosphate-dependent chromodomain helicase DNA binding protein 7, are present in the majority of affected individuals. However, no causal variant can be found in 5-30% (depending on the cohort) of individuals with a clinical diagnosis of CHARGE syndrome. METHODS: We performed whole-exome sequencing (WES) on 28 families from which at least one individual presented with features highly suggestive of CHARGE syndrome. RESULTS: Pathogenic variants in CHD7 were present in 15 of 28 individuals (53.6%), whereas 4 (14.3%) individuals had pathogenic variants in other genes (RERE, KMT2D, EP300, or PUF60). A variant of uncertain clinical significance in KDM6A was identified in one (3.5%) individual. The remaining eight (28.6%) individuals were not found to have pathogenic variants by WES. CONCLUSION: These results demonstrate that the phenotypic features of CHARGE syndrome overlap with multiple other rare single-gene syndromes. Additionally, they implicate a shared molecular pathology that disrupts epigenetic regulation of multiple-organ development.
Keywords: Adolescent; Adult; Carrier Proteins; CHARGE Syndrome; Child; Child, Preschool; Cohort Studies; DNA Helicases; DNA-Binding Proteins; E1A-Associated p300 Protein; Epigenesis, Genetic; Female; Genetic Testing; Humans; Infant; Male; Mutation; Neoplasm Proteins; Phenotype; Repressor Proteins; RNA Splicing Factors

Genetic and mechanistic diversity in pediatric hemophagocytic lymphohistiocytosis. - Chinn, Ivan K; Eckstein, Olive S; Peckham-Gregory, Erin C; Goldberg, Baruch R; Forbes, Lisa R; Nicholas, Sarah K; Mace, Emily M; Vogel, Tiphanie P; Abhyankar, Harshal A; Diaz, Maria I; Heslop, Helen E; Krance, Robert A; et al. (Blood, 2018)
The HLH-2004 criteria are used to diagnose hemophagocytic lymphohistiocytosis (HLH), yet concern exists for their misapplication, resulting in suboptimal treatment of some patients. We sought to define the genomic spectrum and associated outcomes of a diverse cohort of children who met the HLH-2004 criteria. Genetic testing was performed clinically or through research-based whole-exome sequencing. Clinical metrics were analyzed with respect to genomic results. Of 122 subjects enrolled over the course of 17 years, 101 subjects received genetic testing. Biallelic familial HLH (fHLH) gene defects were identified in only 19 (19%) and correlated with presentation at younger than 1 year of age ( < .0001). Digenic fHLH variants were observed but lacked statistical support for disease association. In 28 (58%) of 48 subjects, research whole-exome sequencing analyses successfully identified likely molecular explanations, including underlying primary immunodeficiency diseases, dysregulated immune activation and proliferation disorders, and potentially novel genetic conditions. Two-thirds of patients identified by the HLH-2004 criteria had underlying etiologies for HLH, including genetic defects, autoimmunity, and malignancy. Overall survival was 45%, and increased mortality correlated with HLH triggered by infection or malignancy ( < .05). Differences in survival did not correlate with genetic profile or extent of therapy. HLH should be conceptualized as a phenotype of critical illness characterized by toxic activation of immune cells from different underlying mechanisms. In most patients with HLH, targeted sequencing of fHLH genes remains insufficient for identifying pathogenic mechanisms. Whole-exome sequencing, however, may identify specific therapeutic opportunities and affect hematopoietic stem cell transplantation options for these patients.

Genetic counselors on the frontline of precision health. - Bamshad, Michael J; Magoulas, Pilar L; Dent, Karin M (Am J Med Genet C Semin Med Genet, 2018)
By enabling precise genetic diagnosis and treatment there is great potential for inexpensive, accurate, and widely accessible genomic information to transform health care and improve the general well-being of virtually every person. To maximize this potential, approaches to genetic counseling and the role of genetic counselors will need to adapt to fit changing clinical and commercial needs worldwide. This will require overcoming multiple challenges including an inadequate workforce; development and implementation of alternate models of service delivery; integration of new technologies to improve, extend, and expand services; and support for equitable education and counseling among all populations. Genetic counselors are aptly poised to take on these challenges. The result will be better informed patients and families more capable of utilizing genetic information appropriately, making autonomous decisions about their care, and modifying their approach to disease risk to actively contribute to their health. The contributors to this issue of Seminars discuss how key areas of genetic counseling need to evolve and how genetic counselors can play a role in shaping the future of precision health.

The Genetic Landscape of Diamond-Blackfan Anemia. - Ulirsch, Jacob C; Verboon, Jeffrey M; Kazerounian, Shideh; Guo, Michael H; Yuan, Daniel; Ludwig, Leif S; Handsaker, Robert E; Abdulhay, Nour J; Fiorini, Claudia; Genovese, Giulio; Lim, Elaine T; Cheng, Aaron; et al. (Am J Hum Genet, 2018)
Diamond-Blackfan anemia (DBA) is a rare bone marrow failure disorder that affects 7 out of 1,000,000 live births and has been associated with mutations in components of the ribosome. In order to characterize the genetic landscape of this heterogeneous disorder, we recruited a cohort of 472 individuals with a clinical diagnosis of DBA and performed whole-exome sequencing (WES). We identified relevant rare and predicted damaging mutations for 78% of individuals. The majority of mutations were singletons, absent from population databases, predicted to cause loss of function, and located in 1 of 19 previously reported ribosomal protein (RP)-encoding genes. Using exon coverage estimates, we identified and validated 31 deletions in RP genes. We also observed an enrichment for extended splice site mutations and validated their diverse effects using RNA sequencing in cell lines obtained from individuals with DBA. Leveraging the size of our cohort, we observed robust genotype-phenotype associations with congenital abnormalities and treatment outcomes. We further identified rare mutations in seven previously unreported RP genes that may cause DBA, as well as several distinct disorders that appear to phenocopy DBA, including nine individuals with biallelic CECR1 mutations that result in deficiency of ADA2. However, no new genes were identified at exome-wide significance, suggesting that there are no unidentified genes containing mutations readily identified by WES that explain >5% of DBA-affected case subjects. Overall, this report should inform not only clinical practice for DBA-affected individuals, but also the design and analysis of rare variant studies for heterogeneous Mendelian disorders.

Genetic variants in components of the NALCN-UNC80-UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies). - Bramswig, Nuria C; Bertoli-Avella, Aida M; Albrecht, Beate; Al Aqeel, Aida I; Alhashem, Amal; Al-Sannaa, Nouriya; Bah, Maissa; Bröhl, Katharina; Depienne, Christel; Dorison, Nathalie; Doummar, Diane; Ehmke, Nadja; et al. (Hum Genet, 2018)
NALCN is a conserved cation channel, which conducts a permanent sodium leak current and regulates resting membrane potential and neuronal excitability. It is part of a large ion channel complex, the "NALCN channelosome", consisting of multiple proteins including UNC80 and UNC79. The predominant neuronal expression pattern and its function suggest an important role in neuronal function and disease. So far, biallelic NALCN and UNC80 variants have been described in a small number of individuals leading to infantile hypotonia, psychomotor retardation, and characteristic facies 1 (IHPRF1, OMIM 615419) and 2 (IHPRF2, OMIM 616801), respectively. Heterozygous de novo NALCN missense variants in the S5/S6 pore-forming segments lead to congenital contractures of the limbs and face, hypotonia, and developmental delay (CLIFAHDD, OMIM 616266) with some clinical overlap. In this study, we present detailed clinical information of 16 novel individuals with biallelic NALCN variants, 1 individual with a heterozygous de novo NALCN missense variant and an interesting clinical phenotype without contractures, and 12 individuals with biallelic UNC80 variants. We report for the first time a missense NALCN variant located in the predicted S6 pore-forming unit inherited in an autosomal-recessive manner leading to mild IHPRF1. We show evidence of clinical variability, especially among IHPRF1-affected individuals, and discuss differences between the IHPRF1- and IHPRF2 phenotypes. In summary, we provide a comprehensive overview of IHPRF1 and IHPRF2 phenotypes based on the largest cohort of individuals reported so far and provide additional insights into the clinical phenotypes of these neurodevelopmental diseases to help improve counseling of affected families.
Keywords: Adolescent; Adult; Carrier Proteins; Channelopathies; Child; Child, Preschool; Developmental Disabilities; Female; Genetic Markers; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Phenotype; Sodium Channels; Young Adult

Genotype-phenotype investigation of 35 patients from 11 unrelated families with camptodactyly-arthropathy-coxa vara-pericarditis (CACP) syndrome. - Yilmaz, Saliha; Uludağ Alkaya, Dilek; Kasapcopur, Ozgur; Barut, Kenan; Akdemir, Ekin S; Celen, Cemre; Youngblood, Mark W; Yasuno, Katsuhito; Bilguvar, Kaya; Günel, Murat; Tuysuz, Beyhan (Mol Genet Genomic Med, 2018)
BACKGROUND: The camptodactyly-arthropathy-coxa vara-pericarditis syndrome (CACP) is a rare autosomal recessive condition characterized by camptodactyly, noninflammatory arthropathy, coxa vara, and pericarditis. CACP is caused by mutations in the proteoglycan 4 (PRG4) gene, which encodes a lubricating glycoprotein present in the synovial fluid and at the surface of articular cartilage. METHODS: In the present study, we compared the clinical and molecular findings of CACP syndrome in 35 patients from 11 unrelated families. In 28 patients, whole exome sequencing was used to investigate genomic variations. RESULTS: We found that camptodactyly of hands was the first symptom presented by most patients. Swelling of wrists, knees, and elbows began before 4 years of age, while the age of joint involvement was variable. Patients reported an increased pain level after the age of 10, and severe hip involvement developed after 20 years old. All patients presented developmental coxa vara and seven patients (~22%) had pleural effusion, pericarditis, and/or ascites. We identified nine novel genomic alterations, including the first case of homozygous complete deletion of exon 1 in the PRG4 gene. CONCLUSION: With this study, we contribute to the catalog of CACP causing variants. We confirm that the skeletal component of this disease worsens with age, and presents the potential mechanisms for interfamily variability, by discussing the influence of a modifier gene and escape from nonsense-mediated mRNA decay. We believe that this report will increase awareness of this familial arthropathic condition and the characteristic clinical and radiological findings will facilitate the differentiation from the common childhood rheumatic diseases such as juvenile idiopathic arthritis.
Keywords: Adolescent; Adult; Arthropathy, Neurogenic; Child; Child, Preschool; Coxa Vara; Exons; Female; Genetic Association Studies; Hand Deformities, Congenital; Humans; Male; Middle Aged; Mutation; Proteoglycans; Retrospective Studies; Sequence Deletion; Synovitis; Whole Exome Sequencing

Heterozygous Truncating Variants in POMP Escape Nonsense-Mediated Decay and Cause a Unique Immune Dysregulatory Syndrome. - Poli, M Cecilia; Ebstein, Frédéric; Nicholas, Sarah K; de Guzman, Marietta M; Forbes, Lisa R; Chinn, Ivan K; Mace, Emily M; Vogel, Tiphanie P; Carisey, Alexandre F; Benavides, Felipe; Coban-Akdemir, Zeynep H; Gibbs, Richard A; et al. (Am J Hum Genet, 2018)
The proteasome processes proteins to facilitate immune recognition and host defense. When inherently defective, it can lead to aberrant immunity resulting in a dysregulated response that can cause autoimmunity and/or autoinflammation. Biallelic or digenic loss-of-function variants in some of the proteasome subunits have been described as causing a primary immunodeficiency disease that manifests as a severe dysregulatory syndrome: chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE). Proteasome maturation protein (POMP) is a chaperone for proteasome assembly and is critical for the incorporation of catalytic subunits into the proteasome. Here, we characterize and describe POMP-related autoinflammation and immune dysregulation disease (PRAID) discovered in two unrelated individuals with a unique constellation of early-onset combined immunodeficiency, inflammatory neutrophilic dermatosis, and autoimmunity. We also begin to delineate a complex genetic mechanism whereby de novo heterozygous frameshift variants in the penultimate exon of POMP escape nonsense-mediated mRNA decay (NMD) and result in a truncated protein that perturbs proteasome assembly by a dominant-negative mechanism. To our knowledge, this mechanism has not been reported in any primary immunodeficiencies, autoinflammatory syndromes, or autoimmune diseases. Here, we define a unique hypo- and hyper-immune phenotype and report an immune dysregulation syndrome caused by frameshift mutations that escape NMD.
Keywords: Base Sequence; Cell Line; Endoplasmic Reticulum Stress; Exons; Family; Frameshift Mutation; Genetic Predisposition to Disease; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunophenotyping; Infant, Newborn; Inflammation; Interferon Type I; Male; Molecular Chaperones; Mutant Proteins; Mutation; Nonsense Mediated mRNA Decay; Phenotype; Proteasome Endopeptidase Complex; RNA, Messenger; Syndrome; Unfolded Protein Response

A homozygous founder mutation in associates with a neurodevelopmental disorder characterised by microcephaly, epilepsy and autistic features. - Marin-Valencia, Isaac; Novarino, Gaia; Johansen, Anide; Rosti, Basak; Issa, Mahmoud Y; Musaev, Damir; Bhat, Gifty; Scott, Eric; Silhavy, Jennifer L; Stanley, Valentina; Rosti, Rasim O; Gleeson, Jeremy W; et al. (J Med Genet, 2018)
BACKGROUND: Transport protein particle (TRAPP) is a multisubunit complex that regulates membrane trafficking through the Golgi apparatus. The clinical phenotype associated with mutations in various TRAPP subunits has allowed elucidation of their functions in specific tissues. The role of some subunits in human disease, however, has not been fully established, and their functions remain uncertain. OBJECTIVE: We aimed to expand the range of neurodevelopmental disorders associated with mutations in TRAPP subunits by exome sequencing of consanguineous families. METHODS: Linkage and homozygosity mapping and candidate gene analysis were used to identify homozygous mutations in families. Patient fibroblasts were used to study splicing defect and zebrafish to model the disease. RESULTS: We identified six individuals from three unrelated families with a founder homozygous splice mutation in , encoding a core subunit of the complex TRAPP I. Patients manifested a neurodevelopmental disorder characterised by microcephaly, epilepsy and autistic features, and showed splicing defect. Zebrafish morphants replicated the human phenotype, displaying decreased head size and neuronal hyperexcitability, leading to a lower seizure threshold. CONCLUSION: This study provides clinical and functional evidence of the role of in brain development and function.
Keywords: Animals; Autistic Disorder; Epilepsy; Founder Effect; Genetic Association Studies; Homozygote; Humans; Microcephaly; Mutation; Neurodevelopmental Disorders; Phenotype; Vesicular Transport Proteins; Zebrafish

A homozygous missense mutation in SLC25A16 associated with autosomal recessive isolated fingernail dysplasia in a Pakistani family. - Khan, S; Ansar, M; Khan, A K; Shah, K; Muhammad, N; Shahzad, S; Nickerson, D A; Bamshad, M J; Santos-Cortez, R L P; Leal, S M; Ahmad, W (Br J Dermatol, 2018)

A homozygous missense variant in VWA2, encoding an interactor of the Fraser-complex, in a patient with vesicoureteral reflux. - van der Ven, Amelie T; Kobbe, Birgit; Kohl, Stefan; Shril, Shirlee; Pogoda, Hans-Martin; Imhof, Thomas; Ityel, Hadas; Vivante, Asaf; Chen, Jing; Hwang, Daw-Yang; Connaughton, Dervla M; Mann, Nina; et al. (PLoS One, 2018)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause (40-50%) of chronic kidney disease (CKD) in children. About 40 monogenic causes of CAKUT have so far been discovered. To date less than 20% of CAKUT cases can be explained by mutations in these 40 genes. To identify additional monogenic causes of CAKUT, we performed whole exome sequencing (WES) and homozygosity mapping (HM) in a patient with CAKUT from Indian origin and consanguineous descent. We identified a homozygous missense mutation (c.1336C>T, p.Arg446Cys) in the gene Von Willebrand factor A domain containing 2 (VWA2). With immunohistochemistry studies on kidneys of newborn (P1) mice, we show that Vwa2 and Fraser extracellular matrix complex subunit 1 (Fras1) co-localize in the nephrogenic zone of the renal cortex. We identified a pronounced expression of Vwa2 in the basement membrane of the ureteric bud (UB) and derivatives of the metanephric mesenchyme (MM). By applying in vitro assays, we demonstrate that the Arg446Cys mutation decreases translocation of monomeric VWA2 protein and increases translocation of aggregated VWA2 protein into the extracellular space. This is potentially due to the additional, unpaired cysteine residue in the mutated protein that is used for intermolecular disulfide bond formation. VWA2 is a known, direct interactor of FRAS1 of the Fraser-Complex (FC). FC-encoding genes and interacting proteins have previously been implicated in the pathogenesis of syndromic and/or isolated CAKUT phenotypes in humans. VWA2 therefore constitutes a very strong candidate in the search for novel CAKUT-causing genes. Our results from in vitro experiments indicate a dose-dependent neomorphic effect of the Arg446Cys homozygous mutation in VWA2.
Keywords: Amino Acid Sequence; Amino Acid Substitution; Animals; Animals, Newborn; Biomarkers, Tumor; Child; Consanguinity; Conserved Sequence; Exons; Extracellular Matrix Proteins; Fraser Syndrome; Gene Expression Regulation, Developmental; Homozygote; Humans; Male; Mice; Models, Animal; Models, Molecular; Mutation, Missense; Pedigree; Sequence Homology, Amino Acid; Urogenital Abnormalities; Urogenital System; Vesico-Ureteral Reflux

Identification of a pathogenic PMP2 variant in a multi-generational family with CMT type 1: Clinical gene panels versus genome-wide approaches to molecular diagnosis. - Punetha, Jaya; Mackay-Loder, Loren; Harel, Tamar; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Gibbs, Richard A; Lee, Ian; Terespolsky, Deborah; Lupski, James R; Posey, Jennifer E (Mol Genet Metab, 2018)
Charcot-Marie-Tooth (CMT) disease type 1 is an inherited peripheral neuropathy characterized by demyelination and reduced nerve conduction velocities. We present a multi-generational family with peripheral neuropathy in whom clinical CMT panel testing failed to conclude a molecular diagnosis. We found a PMP2 pathogenic variant c.155T > C, p.(Ile52Thr) that segregates with disease suggesting that PMP2 variants should be considered in patients with neuropathy and that it may be prudent to include in clinical CMT gene panels.

Identification of likely pathogenic and known variants in TSPEAR, LAMB3, BCOR, and WNT10A in four Turkish families with tooth agenesis. - Du, Renqian; Dinckan, Nuriye; Song, Xiaofei; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Guven, Yeliz; Aktoren, Oya; Kayserili, Hülya; Petty, Lauren E; Muzny, Donna M; Below, Jennifer E; Boerwinkle, Eric; et al. (Hum Genet, 2018)
Tooth agenesis (TA), the failure of development of one or more permanent teeth, is a common craniofacial abnormality observed in different world populations. The genetic etiology of TA is heterogeneous; more than a dozen genes have been associated with isolated or nonsyndromic TA, and more than 80 genes with syndromic forms. In this study, we applied whole exome sequencing (WES) to identify candidate genes contributing to TA in four Turkish families. Likely pathogenic variants with a low allele frequency in the general population were identified in four disease-associated genes, including two distinct variants in TSPEAR, associated with syndromic and isolated TA in one family each; a variant in LAMB3 associated with syndromic TA in one family; and a variant in BCOR plus a disease-associated WNT10A variant in one family with syndromic TA. With the notable exception of WNT10A (Tooth agenesis, selective, 4, MIM #150400), the genotype-phenotype relationships described in the present cohort represent an expansion of the clinical spectrum associated with these genes: TSPEAR (Deafness, autosomal recessive 98, MIM #614861), LAMB3 (Amelogenesis imperfecta, type IA, MIM #104530; Epidermolysis bullosa, junctional, MIMs #226700 and #226650), and BCOR (Microphthalmia, syndromic 2, MIM #300166). We provide evidence supporting the candidacy of these genes with TA, and propose TSPEAR as a novel nonsyndromic TA gene. Our data also suggest potential multilocus genomic variation, or mutational burden, in a single family, involving the BCOR and WNT10A loci, underscoring the complexity of the genotype-phenotype relationship in the common complex trait of TA.
Keywords: Anodontia; Cell Adhesion Molecules; Child; Child, Preschool; Female; Genetic Markers; Humans; Male; Mutation; Pedigree; Phenotype; Proteins; Proto-Oncogene Proteins; Repressor Proteins; Turkey; Wnt Proteins

Identifying Genes Whose Mutant Transcripts Cause Dominant Disease Traits by Potential Gain-of-Function Alleles. - Coban-Akdemir, Zeynep; White, Janson J; Song, Xiaofei; Jhangiani, Shalini N; Fatih, Jawid M; Gambin, Tomasz; Bayram, Yavuz; Chinn, Ivan K; Karaca, Ender; Punetha, Jaya; Poli, Cecilia; Boerwinkle, Eric; et al. (Am J Hum Genet, 2018)
Premature termination codon (PTC)-bearing transcripts are often degraded by nonsense-mediated decay (NMD) resulting in loss-of-function (LoF) alleles. However, not all PTCs result in LoF mutations, i.e., some such transcripts escape NMD and are translated to truncated peptide products that result in disease due to gain-of-function (GoF) effects. Since the location of the PTC is a major factor determining transcript fate, we hypothesized that depletion of protein-truncating variants (PTVs) within the gene region predicted to escape NMD in control databases could provide a rank for genic susceptibility for disease through GoF versus LoF. We developed an NMD escape intolerance score to rank genes based on the depletion of PTVs that would render them able to escape NMD using the Atherosclerosis Risk in Communities Study (ARIC) and the Exome Aggregation Consortium (ExAC) control databases, which was further used to screen the Baylor-Center for Mendelian Genomics disease database. This analysis revealed 1,996 genes significantly depleted for PTVs that are predicted to escape from NMD, i.e., PTVesc; further studies provided evidence that revealed a subset as candidate genes underlying Mendelian phenotypes. Importantly, these genes have characteristically low pLI scores, which can cause them to be overlooked as candidates for dominant diseases. Collectively, we demonstrate that this NMD escape intolerance score is an effective and efficient tool for gene discovery in Mendelian diseases due to production of truncated or altered proteins. More importantly, we provide a complementary analytical tool to aid identification of genes associated with dominant traits through a mechanism distinct from LoF.

Insights into clonal haematopoiesis from 8,342 mosaic chromosomal alterations. - Loh, Po-Ru; Genovese, Giulio; Handsaker, Robert E; Finucane, Hilary K; Reshef, Yakir A; Palamara, Pier Francesco; Birmann, Brenda M; Talkowski, Michael E; Bakhoum, Samuel F; McCarroll, Steven A; Price, Alkes L (Nature, 2018)
The selective pressures that shape clonal evolution in healthy individuals are largely unknown. Here we investigate 8,342 mosaic chromosomal alterations, from 50 kb to 249 Mb long, that we uncovered in blood-derived DNA from 151,202 UK Biobank participants using phase-based computational techniques (estimated false discovery rate, 6-9%). We found six loci at which inherited variants associated strongly with the acquisition of deletions or loss of heterozygosity in cis. At three such loci (MPL, TM2D3-TARSL2, and FRA10B), we identified a likely causal variant that acted with high penetrance (5-50%). Inherited alleles at one locus appeared to affect the probability of somatic mutation, and at three other loci to be objects of positive or negative clonal selection. Several specific mosaic chromosomal alterations were strongly associated with future haematological malignancies. Our results reveal a multitude of paths towards clonal expansions with a wide range of effects on human health.
Keywords: Adult; Aged; Alleles; Biological Specimen Banks; Chromosome Aberrations; Chromosome Breakage; Chromosome Fragile Sites; Chromosomes, Human, Pair 10; Clone Cells; Female; Health; Hematologic Neoplasms; Hematopoiesis; Humans; Male; Middle Aged; Mosaicism; Penetrance; United Kingdom

Loss of Protocadherin-12 Leads to Diencephalic-Mesencephalic Junction Dysplasia Syndrome. - Guemez-Gamboa, Alicia; Çağlayan, Ahmet Okay; Stanley, Valentina; Gregor, Anne; Zaki, Maha S; Saleem, Sahar N; Musaev, Damir; McEvoy-Venneri, Jennifer; Belandres, Denice; Akizu, Naiara; Silhavy, Jennifer L; Schroth, Jana; et al. (Ann Neurol, 2018)
OBJECTIVE: To identify causes of the autosomal-recessive malformation, diencephalic-mesencephalic junction dysplasia (DMJD) syndrome. METHODS: Eight families with DMJD were studied by whole-exome or targeted sequencing, with detailed clinical and radiological characterization. Patient-derived induced pluripotent stem cells were derived into neural precursor and endothelial cells to study gene expression. RESULTS: All patients showed biallelic mutations in the nonclustered protocadherin-12 (PCDH12) gene. The characteristic clinical presentation included progressive microcephaly, craniofacial dysmorphism, psychomotor disability, epilepsy, and axial hypotonia with variable appendicular spasticity. Brain imaging showed brainstem malformations and with frequent thinned corpus callosum with punctate brain calcifications, reflecting expression of PCDH12 in neural and endothelial cells. These cells showed lack of PCDH12 expression and impaired neurite outgrowth. INTERPRETATION: DMJD patients have biallelic mutations in PCDH12 and lack of protein expression. These patients present with characteristic microcephaly and abnormalities of white matter tracts. Such pathogenic variants predict a poor outcome as a result of brainstem malformation and evidence of white matter tract defects, and should be added to the phenotypic spectrum associated with PCDH12-related conditions. Ann Neurol 2018;84:646-655.

Loss of tubulin deglutamylase CCP1 causes infantile-onset neurodegeneration. - Shashi, Vandana; Magiera, Maria M; Klein, Dennis; Zaki, Maha; Schoch, Kelly; Rudnik-Schöneborn, Sabine; Norman, Andrew; Lopes Abath Neto, Osorio; Dusl, Marina; Yuan, Xidi; Bartesaghi, Luca; De Marco, Patrizia; et al. (EMBO J, 2018)
A set of glutamylases and deglutamylases controls levels of tubulin polyglutamylation, a prominent post-translational modification of neuronal microtubules. Defective tubulin polyglutamylation was first linked to neurodegeneration in the () mouse, which lacks deglutamylase CCP1, displays massive cerebellar atrophy, and accumulates abnormally glutamylated tubulin in degenerating neurons. We found biallelic rare and damaging variants in the gene encoding CCP1 in 13 individuals with infantile-onset neurodegeneration and confirmed the absence of functional CCP1 along with dysregulated tubulin polyglutamylation. The human disease mainly affected the cerebellum, spinal motor neurons, and peripheral nerves. We also demonstrate previously unrecognized peripheral nerve and spinal motor neuron degeneration in mice, which thus recapitulated key features of the human disease. Our findings link human neurodegeneration to tubulin polyglutamylation, entailing this post-translational modification as a potential target for drug development for neurodegenerative disorders.

LTBP3 Pathogenic Variants Predispose Individuals to Thoracic Aortic Aneurysms and Dissections. - Guo, Dong-Chuan; Regalado, Ellen S; Pinard, Amelie; Chen, Jiyuan; Lee, Kwanghyuk; Rigelsky, Christina; Zilberberg, Lior; Hostetler, Ellen M; Aldred, Micheala; Wallace, Stephanie E; Prakash, Siddharth K; Leal, Suzanne M; et al. (Am J Hum Genet, 2018)
The major diseases affecting the thoracic aorta are aneurysms and acute dissections, and pathogenic variants in 11 genes are confirmed to lead to heritable thoracic aortic disease. However, many families in which multiple members have thoracic aortic disease do not have alterations in the known aortopathy genes. Genes highly expressed in the aorta were assessed for rare variants in exome sequencing data from such families, and compound rare heterozygous variants (p.Pro45Argfs25 and p.Glu750) in LTBP3 were identified in affected members of one family. A homozygous variant (p.Asn678_Gly681delinsThrCys) that introduces an additional cysteine into an epidermal growth factor (EGF)-like domain in the corresponding protein, latent TGF-β binding protein (LTBP-3), was identified in a second family. Individuals with compound heterozygous or homozygous variants in these families have aneurysms and dissections of the thoracic aorta, as well as aneurysms of the abdominal aorta and other arteries, along with dental abnormalities and short stature. Heterozygous carriers of the p.Asn678_Gly681delinsThrCys variant have later onset of thoracic aortic disease, as well as dental abnormalities. In these families, LTBP3 variants segregated with thoracic aortic disease with a combined LOD score of 3.9. Additionally, heterozygous rare LTBP3 variants were found in individuals with early onset of acute aortic dissections, and some of these variants disrupted LTBP-3 levels or EGF-like domains. When compared to wild-type mice, Ltbp3 mice have enlarged aortic roots and ascending aortas. In summary, homozygous LTBP3 pathogenic variants predispose individuals to thoracic aortic aneurysms and dissections, along with the previously described skeletal and dental abnormalities.
Keywords: Adult; Aged, 80 and over; Aneurysm, Dissecting; Animals; Aortic Aneurysm, Thoracic; Blood Pressure; Female; Genetic Predisposition to Disease; Homozygote; Humans; Latent TGF-beta Binding Proteins; Male; Mice; Middle Aged; Mutation; Pedigree

MACF1 Mutations Encoding Highly Conserved Zinc-Binding Residues of the GAR Domain Cause Defects in Neuronal Migration and Axon Guidance. - Dobyns, William B; Aldinger, Kimberly A; Ishak, Gisele E; Mirzaa, Ghayda M; Timms, Andrew E; Grout, Megan E; Dremmen, Marjolein H G; Schot, Rachel; Vandervore, Laura; van Slegtenhorst, Marjon A; Wilke, Martina; Kasteleijn, Esmee; et al. (Am J Hum Genet, 2018)
To date, mutations in 15 actin- or microtubule-associated genes have been associated with the cortical malformation lissencephaly and variable brainstem hypoplasia. During a multicenter review, we recognized a rare lissencephaly variant with a complex brainstem malformation in three unrelated children. We searched our large brain-malformation databases and found another five children with this malformation (as well as one with a less severe variant), analyzed available whole-exome or -genome sequencing data, and tested ciliogenesis in two affected individuals. The brain malformation comprised posterior predominant lissencephaly and midline crossing defects consisting of absent anterior commissure and a striking W-shaped brainstem malformation caused by small or absent pontine crossing fibers. We discovered heterozygous de novo missense variants or an in-frame deletion involving highly conserved zinc-binding residues within the GAR domain of MACF1 in the first eight subjects. We studied cilium formation and found a higher proportion of mutant cells with short cilia than of control cells with short cilia. A ninth child had similar lissencephaly but only subtle brainstem dysplasia associated with a heterozygous de novo missense variant in the spectrin repeat domain of MACF1. Thus, we report variants of the microtubule-binding GAR domain of MACF1 as the cause of a distinctive and most likely pathognomonic brain malformation. A gain-of-function or dominant-negative mechanism appears likely given that many heterozygous mutations leading to protein truncation are included in the ExAC Browser. However, three de novo variants in MACF1 have been observed in large schizophrenia cohorts.

Marker chromosome genomic structure and temporal origin implicate a chromoanasynthesis event in a family with pleiotropic psychiatric phenotypes. - Grochowski, Christopher M; Gu, Shen; Yuan, Bo; Tcw, Julia; Brennand, Kristen J; Sebat, Jonathan; Malhotra, Dheeraj; McCarthy, Shane; Rudolph, Uwe; Lindstrand, Anna; Chong, Zechen; Levy, Deborah L; et al. (Hum Mutat, 2018)
Small supernumerary marker chromosomes (sSMC) are chromosomal fragments difficult to characterize genomically. Here, we detail a proband with schizoaffective disorder and a mother with bipolar disorder with psychotic features who present with a marker chromosome that segregates with disease. We explored the architecture of this marker and investigated its temporal origin. Array comparative genomic hybridization (aCGH) analysis revealed three duplications and three triplications that spanned the short arm of chromosome 9, suggestive of a chromoanasynthesis-like event. Segregation of marker genotypes, phased using sSMC mosaicism in the mother, provided evidence that it was generated during a germline-level event in the proband's maternal grandmother. Whole-genome sequencing (WGS) was performed to resolve the structure and junctions of the chromosomal fragments, revealing further complexities. While structural variations have been previously associated with neuropsychiatric disorders and marker chromosomes, here we detail the precise architecture, human life-cycle genesis, and propose a DNA replicative/repair mechanism underlying formation.

matchbox: An open-source tool for patient matching via the Matchmaker Exchange. - Arachchi, Harindra; Wojcik, Monica H; Weisburd, Benjamin; Jacobsen, Julius O B; Valkanas, Elise; Baxter, Samantha; Byrne, Alicia B; O'Donnell-Luria, Anne H; Haendel, Melissa; Smedley, Damian; MacArthur, Daniel G; Philippakis, Anthony A; et al. (Hum Mutat, 2018)
Rare disease investigators constantly face challenges in identifying additional cases to build evidence for gene-disease causality. The Matchmaker Exchange (MME) addresses this limitation by providing a mechanism for matching patients across genomic centers via a federated network. The MME has revolutionized searching for additional cases by making it possible to query across institutional boundaries, so that what was once a laborious and manual process of contacting researchers is now automated and computable. However, while the MME network is beginning to scale, the growth of additional nodes is limited by the lack of easy-to-use solutions that can be implemented by any rare disease database owner, even one without significant software engineering resources. Here, we describe matchbox, which is an open-source, platform-independent, portable bridge between any given rare disease genomic center and the MME network, which has already led to novel gene discoveries. We also describe how matchbox greatly reduces the barrier to participation by overcoming challenges for new databases to join the MME.

Monoallelic and biallelic CREB3L1 variant causes mild and severe osteogenesis imperfecta, respectively. - Keller, Rachel B; Tran, Thao T; Pyott, Shawna M; Pepin, Melanie G; Savarirayan, Ravi; McGillivray, George; Nickerson, Deborah A; Bamshad, Michael J; Byers, Peter H (Genet Med, 2018)
PurposeOsteogenesis imperfecta (OI) is a heritable skeletal dysplasia. Dominant pathogenic variants in COL1A1 and COL1A2 explain the majority of OI cases. At least 15 additional genes have been identified, but those still do not account for all OI phenotypes that present. We sought the genetic cause of mild and lethal OI phenotypes in an unsolved family.MethodsWe performed exome sequencing on seven members of the family, both affected and unaffected.ResultsWe identified a variant in cyclic AMP responsive element binding protein 3-like 1 (CREB3L1) in a consanguineous family. The variant caused a prenatal/perinatal lethal OI in homozygotes, similar to that seen in OI type II as a result of mutations in type I collagen genes, and a mild phenotype (fractures, blue sclerae) in multiple heterozygous family members. CREB3L1 encodes old astrocyte specifically induced substance (OASIS), an endoplasmic reticulum stress transducer. The variant disrupts a DNA-binding site and prevents OASIS from acting on its transcriptional targets including SEC24D, which encodes a component of the coat protein II complex.ConclusionThis report confirms that CREB3L1 is an OI-related gene and suggests the pathogenic mechanism of CREB3L1-associated OI involves the altered regulation of proteins involved in cellular secretion.
Keywords: Alleles; Amino Acid Sequence; Collagen Type I; Cyclic AMP Response Element-Binding Protein; DNA Mutational Analysis; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Mutation; Nerve Tissue Proteins; Osteogenesis Imperfecta; Pedigree; Phenotype; Radiography; Sequence Analysis, DNA; Severity of Illness Index; Ultrasonography, Prenatal

Monoallelic Mutations to DNAJB11 Cause Atypical Autosomal-Dominant Polycystic Kidney Disease. - Cornec-Le Gall, Emilie; Olson, Rory J; Besse, Whitney; Heyer, Christina M; Gainullin, Vladimir G; Smith, Jessica M; Audrézet, Marie-Pierre; Hopp, Katharina; Porath, Binu; Shi, Beili; Baheti, Saurabh; Senum, Sarah R; et al. (Am J Hum Genet, 2018)
Autosomal-dominant polycystic kidney disease (ADPKD) is characterized by the progressive development of kidney cysts, often resulting in end-stage renal disease (ESRD). This disorder is genetically heterogeneous with ∼7% of families genetically unresolved. We performed whole-exome sequencing (WES) in two multiplex ADPKD-like pedigrees, and we analyzed a further 591 genetically unresolved, phenotypically similar families by targeted next-generation sequencing of 65 candidate genes. WES identified a DNAJB11 missense variant (p.Pro54Arg) in two family members presenting with non-enlarged polycystic kidneys and a frameshifting change (c.166_167insTT) in a second family with small renal and liver cysts. DNAJB11 is a co-factor of BiP, a key chaperone in the endoplasmic reticulum controlling folding, trafficking, and degradation of secreted and membrane proteins. Five additional multigenerational families carrying DNAJB11 mutations were identified by the targeted analysis. The clinical phenotype was consistent in the 23 affected members, with non-enlarged cystic kidneys that often evolved to kidney atrophy; 7 subjects reached ESRD from 59 to 89 years. The lack of kidney enlargement, histologically evident interstitial fibrosis in non-cystic parenchyma, and recurring episodes of gout (one family) suggested partial phenotypic overlap with autosomal-dominant tubulointerstitial diseases (ADTKD). Characterization of DNAJB11-null cells and kidney samples from affected individuals revealed a pathogenesis associated with maturation and trafficking defects involving the ADPKD protein, PC1, and ADTKD proteins, such as UMOD. DNAJB11-associated disease is a phenotypic hybrid of ADPKD and ADTKD, characterized by normal-sized cystic kidneys and progressive interstitial fibrosis resulting in late-onset ESRD.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Amino Acid Sequence; Base Sequence; Epithelial Cells; Family; Female; HSP40 Heat-Shock Proteins; Humans; Loop of Henle; Male; Middle Aged; Mutation; Pedigree; Polycystic Kidney, Autosomal Dominant; TRPP Cation Channels; Uromodulin; Whole Exome Sequencing; Young Adult

Multigenic Disease and Bilineal Inheritance in Dilated Cardiomyopathy Is Illustrated in Nonsegregating LMNA Pedigrees. - Cowan, Jason R; Kinnamon, Daniel D; Morales, Ana; Salyer, Lorien; Nickerson, Deborah A; Hershberger, Ray E (Circ Genom Precis Med, 2018)
BACKGROUND: We have previously described 19 pedigrees with apparent lamin ()-related dilated cardiomyopathy (DCM) manifesting in affected family members across multiple generations. In 6 of 19 families, at least 1 individual with idiopathic DCM did not carry the family's variant. We hypothesized that additional genetic cause may underlie DCM in these families. METHODS: Affected family members underwent exome sequencing to identify additional genetic cause of DCM in the 6 families with nonsegregating variants. RESULTS: In 5 of 6 pedigrees, we identified at least 1 additional rare variant in a known DCM gene that could plausibly contribute to disease in the variant-negative individuals. Bilineal inheritance was clear or presumed to be present in 3 of 5 families and was possible in the remaining 2. At least 1 individual with a variant also carried a variant in an additional identified DCM gene in each family. Using a multivariate linear mixed model for quantitative traits, we demonstrated that the presence of these additional variants was associated with a more severe phenotype after adjusting for sex, age, and the presence/absence of the family's nonsegregating variant. CONCLUSIONS: Our data support DCM as a genetically heterogeneous disease with, at times, multigene causation. Although the frequency of DCM resulting from multigenic cause is uncertain, our data suggest it may be higher than previously anticipated.

Mutation in the intracellular chloride channel CLCC1 associated with autosomal recessive retinitis pigmentosa. - Li, Lin; Jiao, Xiaodong; D'Atri, Ilaria; Ono, Fumihito; Nelson, Ralph; Chan, Chi-Chao; Nakaya, Naoki; Ma, Zhiwei; Ma, Yan; Cai, Xiaoying; Zhang, Longhua; Lin, Siying; et al. (PLoS Genet, 2018)
We identified a homozygous missense alteration (c.75C>A, p.D25E) in CLCC1, encoding a presumptive intracellular chloride channel highly expressed in the retina, associated with autosomal recessive retinitis pigmentosa (arRP) in eight consanguineous families of Pakistani descent. The p.D25E alteration decreased CLCC1 channel function accompanied by accumulation of mutant protein in granules within the ER lumen, while siRNA knockdown of CLCC1 mRNA induced apoptosis in cultured ARPE-19 cells. TALEN KO in zebrafish was lethal 11 days post fertilization. The depressed electroretinogram (ERG) cone response and cone spectral sensitivity of 5 dpf KO zebrafish and reduced eye size, retinal thickness, and expression of rod and cone opsins could be rescued by injection of wild type CLCC1 mRNA. Clcc1+/- KO mice showed decreased ERGs and photoreceptor number. Together these results strongly suggest that intracellular chloride transport by CLCC1 is a critical process in maintaining retinal integrity, and CLCC1 is crucial for survival and function of retinal cells.
Keywords: Animals; Asian Continental Ancestry Group; Cell Line; Chloride Channels; Cytoplasm; Eye Proteins; HEK293 Cells; Homozygote; Humans; Mice; Mice, Knockout; Mutation, Missense; Pakistan; Retina; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa; Zebrafish

Mutations in LNPK, Encoding the Endoplasmic Reticulum Junction Stabilizer Lunapark, Cause a Recessive Neurodevelopmental Syndrome. - Breuss, Martin W; Nguyen, An; Song, Qiong; Nguyen, Thai; Stanley, Valentina; James, Kiely N; Musaev, Damir; Chai, Guoliang; Wirth, Sara A; Anzenberg, Paula; George, Renee D; Johansen, Anide; et al. (Am J Hum Genet, 2018)
The dynamic shape of the endoplasmic reticulum (ER) is a reflection of its wide variety of critical cell biological functions. Consequently, perturbation of ER-shaping proteins can cause a range of human phenotypes. Here, we describe three affected children (from two consanguineous families) who carry homozygous loss-of-function mutations in LNPK (previously known as KIAA1715); this gene encodes lunapark, which is proposed to serve as a curvature-stabilizing protein within tubular three-way junctions of the ER. All individuals presented with severe psychomotor delay, intellectual disability, hypotonia, epilepsy, and corpus callosum hypoplasia, and two of three showed mild cerebellar hypoplasia and atrophy. Consistent with a proposed role in neurodevelopmental disease, LNPK was expressed during brain development in humans and mice and was present in neurite-like processes in differentiating human neural progenitor cells. Affected cells showed the absence of full-length lunapark, aberrant ER structures, and increased luminal mass density. Together, our results implicate the ER junction stabilizer lunapark in establishing the corpus callosum.

Mutations in multiple components of the nuclear pore complex cause nephrotic syndrome. - Braun, Daniela A; Lovric, Svjetlana; Schapiro, David; Schneider, Ronen; Marquez, Jonathan; Asif, Maria; Hussain, Muhammad Sajid; Daga, Ankana; Widmeier, Eugen; Rao, Jia; Ashraf, Shazia; Tan, Weizhen; et al. (J Clin Invest, 2018)
Steroid-resistant nephrotic syndrome (SRNS) almost invariably progresses to end-stage renal disease. Although more than 50 monogenic causes of SRNS have been described, a large proportion of SRNS remains unexplained. Recently, it was discovered that mutations of NUP93 and NUP205, encoding 2 proteins of the inner ring subunit of the nuclear pore complex (NPC), cause SRNS. Here, we describe mutations in genes encoding 4 components of the outer rings of the NPC, namely NUP107, NUP85, NUP133, and NUP160, in 13 families with SRNS. Using coimmunoprecipitation experiments, we showed that certain pathogenic alleles weakened the interaction between neighboring NPC subunits. We demonstrated that morpholino knockdown of nup107, nup85, or nup133 in Xenopus disrupted glomerulogenesis. Re-expression of WT mRNA, but not of mRNA reflecting mutations from SRNS patients, mitigated this phenotype. We furthermore found that CRISPR/Cas9 knockout of NUP107, NUP85, or NUP133 in podocytes activated Cdc42, an important effector of SRNS pathogenesis. CRISPR/Cas9 knockout of nup107 or nup85 in zebrafish caused developmental anomalies and early lethality. In contrast, an in-frame mutation of nup107 did not affect survival, thus mimicking the allelic effects seen in humans. In conclusion, we discovered here that mutations in 4 genes encoding components of the outer ring subunits of the NPC cause SRNS and thereby provide further evidence that specific hypomorphic mutations in these essential genes cause a distinct, organ-specific phenotype.

Mutations in PI3K110δ cause impaired natural killer cell function partially rescued by rapamycin treatment. - Ruiz-García, Raquel; Vargas-Hernandez, Alexander; Chinn, Ivan K; Angelo, Laura S; Cao, Tram N; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Meng, Qingchang; Forbes, Lisa R; Muzny, Donna M; Allende, Luis M; Ehlayel, Mohammed S; et al. (J Allergy Clin Immunol, 2018)
BACKGROUND: Heterozygous gain-of-function mutations in PI3K110δ lead to lymphadenopathy, lymphoid hyperplasia, EBV and cytomegalovirus viremia, and sinopulmonary infections. OBJECTIVE: The known role of natural killer (NK) cell function in the control of EBV and cytomegalovirus prompted us to investigate the functional and phenotypic effects of PI3K110δ mutations on NK cell subsets and cytotoxic function. METHODS: Mutations in patients were identified by using whole-exome or targeted sequencing. We performed NK cell phenotyping and functional analysis of patients' cells using flow cytometry, standard Cr cytotoxicity assays, and quantitative confocal microscopy. RESULTS: PI3K110δ mutations led to an altered NK cell developmental phenotype and cytotoxic dysfunction. Impaired NK cell cytotoxicity was due to decreased conjugate formation with susceptible target cells and abrogated activation of cell machinery required for target cell killing. These defects were restored partially after initiation of treatment with rapamycin in 3 patients. CONCLUSION: We describe novel NK cell functional deficiency caused by PI3K110δ mutation, which is a likely contributor to the severe viremia observed in these patients. Rapamycin treatment partially restores NK cell function, providing a further rationale for its use in patients with this disease.

Mutations in the Epithelial Cadherin-p120-Catenin Complex Cause Mendelian Non-Syndromic Cleft Lip with or without Cleft Palate. - Cox, Liza L; Cox, Timothy C; Moreno Uribe, Lina M; Zhu, Ying; Richter, Chika T; Nidey, Nichole; Standley, Jennifer M; Deng, Mei; Blue, Elizabeth; Chong, Jessica X; Yang, Yueqin; Carstens, Russ P; et al. (Am J Hum Genet, 2018)
Non-syndromic cleft lip with or without cleft palate (NS-CL/P) is one of the most common human birth defects and is generally considered a complex trait. Despite numerous loci identified by genome-wide association studies, the effect sizes of common variants are relatively small, with much of the presumed genetic contribution remaining elusive. We report exome-sequencing results in 209 people from 72 multi-affected families with pedigree structures consistent with autosomal-dominant inheritance and variable penetrance. Herein, pathogenic variants are described in four genes encoding components of the p120-catenin complex (CTNND1, PLEKHA7, PLEKHA5) and an epithelial splicing regulator (ESRP2), in addition to the known CL/P-associated gene, CDH1, which encodes E-cadherin. The findings were also validated in a second cohort of 497 people with NS-CL/P, comprising small families and singletons with pathogenic variants in these genes identified in 14% of multi-affected families and 2% of the replication cohort of smaller families. Enriched expression of each gene/protein in human and mouse embryonic oro-palatal epithelia, demonstration of functional impact of CTNND1 and ESRP2 variants, and recapitulation of the CL/P spectrum in Ctnnd1 knockout mice support a causative role in CL/P pathogenesis. These data show that primary defects in regulators of epithelial cell adhesion are the most significant contributors to NS-CL/P identified to date and that inherited and de novo single gene variants explain a substantial proportion of NS-CL/P.
Keywords: Alleles; Amino Acid Sequence; Animals; Biotinylation; Cadherins; Catenins; Cleft Lip; Cleft Palate; Epithelium; Female; Gene Deletion; Genetic Predisposition to Disease; Humans; Infant; Infant, Newborn; Male; Mice; Mutation; Palate; Pedigree; Syndrome; Whole Exome Sequencing

Mutations in the fourth β-propeller domain of LRP4 are associated with isolated syndactyly with fusion of the third and fourth fingers. - Sukenik Halevy, Rivka; Chien, Huan-Chieh; Heinz, Bo; Bamshad, Michael J; Nickerson, Deborah A; Kircher, Martin; Ahituv, Nadav (Hum Mutat, 2018)
Isolated hand syndactyly is a common limb malformation with limited known genetic etiology. We used exome sequencing to discover two novel variants, chr11 g.46896373C>G; p.D1403H and chr11 g.46893078G>T; p.Q1564K, in LRP4 in a child with isolated bilateral syndactyly of the third and fourth fingers. Each variant was inherited from a different parent and neither parent was affected. Variants in LRP4 have been previously associated with syndactyly in Cenani-Lenz syndactyly syndrome and Sclerosteosis 2, but have not been reported in individuals with isolated syndactyly. LRP4 inhibits LRP6/LRP5-mediated activation of canonical Wnt signaling and mediates sclerostin-dependent inhibition of bone formation. p.D1403H and p.Q1564K are located within the fourth β-propeller of the extracellular protein domain that has yet to be associated with human disease. Functional analyses of p.D1403H and p.Q1564K show that they significantly decrease LRP4's inhibition of Wnt signaling. These results suggest that variants in the fourth β-propeller of the extracellular protein domain may cause a phenotype distinct from previously characterized LRP4 variants.

Mutations in the mitochondrial ribosomal protein MRPS22 lead to primary ovarian insufficiency. - Chen, Anlu; Tiosano, Dov; Guran, Tulay; Baris, Hagit N; Bayram, Yavuz; Mory, Adi; Shapiro-Kulnane, Laura; Hodges, Craig A; Akdemir, Zeynep C; Turan, Serap; Jhangiani, Shalini N; van den Akker, Focco; et al. (Hum Mol Genet, 2018)
Primary ovarian insufficiency (POI) is characterized by amenorrhea and loss or dysfunction of ovarian follicles prior to the age of 40. POI has been associated with autosomal recessive mutations in genes involving hormonal signaling and folliculogenesis, however, the genetic etiology of POI most often remains unknown. Here we report MRPS22 homozygous missense variants c.404G>A (p.R135Q) and c.605G>A (p.R202H) identified in four females from two independent consanguineous families as a novel genetic cause of POI in adolescents. Both missense mutations identified in MRPS22 are rare, occurred in highly evolutionarily conserved residues, and are predicted to be deleterious to protein function. In contrast to prior reports of mutations in MRPS22 associated with severe mitochondrial disease, the POI phenotype is far less severe. Consistent with this genotype-phenotype correlation, mitochondrial defects in oxidative phosphorylation or rRNA levels were not detected in fibroblasts derived from the POI patients, suggesting a non-bioenergetic or tissue-specific mitochondrial defect. Furthermore, we demonstrate in a Drosophila model that mRpS22 deficiency specifically in somatic cells of the ovary had no effect on fertility, whereas flies with mRpS22 deficiency specifically in germ cells were infertile and agametic, demonstrating a cell autonomous requirement for mRpS22 in germ cell development. These findings collectively identify that MRPS22, a component of the small mitochondrial ribosome subunit, is critical for ovarian development and may therefore provide insight into the pathophysiology and treatment of ovarian dysfunction.
Keywords: Adolescent; Adult; Amenorrhea; Animals; Disease Models, Animal; Drosophila; Drosophila Proteins; Female; Fertility; Homozygote; Humans; Menopause, Premature; Mitochondrial Proteins; Mutation, Missense; Ovarian Follicle; Primary Ovarian Insufficiency; Ribosomal Proteins; Young Adult

Mutations in WDR4 as a new cause of Galloway-Mowat syndrome. - Braun, Daniela A; Shril, Shirlee; Sinha, Aditi; Schneider, Ronen; Tan, Weizhen; Ashraf, Shazia; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; Majmundar, Amar J; Daga, Ankana; Warejko, Jillian K; et al. (Am J Med Genet A, 2018)
Galloway-Mowat syndrome (GAMOS) is a phenotypically heterogeneous disorder characterized by neurodevelopmental defects combined with renal-glomerular disease, manifesting with proteinuria. To identify additional monogenic disease causes, we here performed whole exome sequencing (WES), linkage analysis, and homozygosity mapping in three affected siblings of an Indian family with GAMOS. Applying established criteria for variant filtering, we identify a novel homozygous splice site mutation in the gene WDR4 as the likely disease-causing mutation in this family. In line with previous reports, we observe growth deficiency, microcephaly, developmental delay, and intellectual disability as phenotypic features resulting from WDR4 mutations. However, the newly identified allele additionally gives rise to proteinuria and nephrotic syndrome, a phenotype that was never reported in patients with WDR4 mutations. Our data thus expand the phenotypic spectrum of WDR4 mutations by demonstrating that, depending on the specific mutated allele, a renal phenotype may be present. This finding suggests that GAMOS may occupy a phenotypic spectrum with other microcephalic diseases. Furthermore, WDR4 is an additional example of a gene that encodes a tRNA modifying enzyme and gives rise to GAMOS, if mutated. Our findings thereby support the recent observation that, like neurons, podocytes of the renal glomerulus are particularly vulnerable to cellular defects resulting from altered tRNA modifications.

Nemaline myopathy and distal arthrogryposis associated with an autosomal recessive TNNT3 splice variant. - Sandaradura, Sarah A; Bournazos, Adam; Mallawaarachchi, Amali; Cummings, Beryl B; Waddell, Leigh B; Jones, Kristi J; Troedson, Christopher; Sudarsanam, Annapurna; Nash, Benjamin M; Peters, Gregory B; Algar, Elizabeth M; MacArthur, Daniel G; et al. (Hum Mutat, 2018)
A male neonate presented with severe weakness, hypotonia, contractures and congenital scoliosis. Skeletal muscle specimens showed marked atrophy and degeneration of fast fibers with striking nemaline rods and hypertrophy of slow fibers that were ultrastructurally normal. A neuromuscular gene panel identified a homozygous essential splice variant in TNNT3 (chr11:1956150G > A, NM_006757.3:c.681+1G > A). TNNT3 encodes skeletal troponin-T and is associated with autosomal dominant distal arthrogryposis. TNNT3 has not previously been associated with nemaline myopathy (NM), a rare congenital myopathy linked to defects in proteins associated with thin filament structure and regulation. cDNA studies confirmed pathogenic consequences of the splice variant, eliciting exon-skipping and intron retention events leading to a frameshift. Western blot showed deficiency of troponin-T protein with secondary loss of troponin-I . We establish a homozygous splice variant in TNNT3 as the likely cause of severe congenital NM with distal arthrogryposis, characterized by specific involvement of Type-2 fibers and deficiency of troponin-T .
Keywords: Arthrogryposis; Genes, Recessive; Humans; Infant; Infant, Newborn; Male; Myopathies, Nemaline; RNA Splice Sites; RNA Splicing; RNA, Messenger; Troponin T

A noncoding variant in GANAB explains isolated polycystic liver disease (PCLD) in a large family. - Besse, Whitney; Choi, Jungmin; Ahram, Dina; Mane, Shrikant; Sanna-Cherchi, Simone; Torres, Vicente; Somlo, Stefan (Hum Mutat, 2018)
Expanded mutation detection and novel gene discovery for isolated polycystic liver disease (PCLD) are necessary as 50% of cases do not have identified mutations in the seven published disease genes. We investigated a family with five affected siblings for which no loss-of-function variants were identified by whole exome sequencing analysis. SNP genotyping and linkage analysis narrowed the candidate regions to ∼8% of the genome, which included two published PCLD genes in close proximity to each other, GANAB and LRP5. Based on these findings, we re-evaluated the exome sequencing data and identified a novel intronic nine base pair deletion in the vicinity of the GANAB exon 24 splice donor that had initially been discarded by the sequence analysis pipelines. We used a minigene assay to show that this deletion leads to skipping of exon 24 in cell lines and primary human cholangiocytes. These findings prompt genomic evaluation beyond the coding region to enhance mutation detection in PCLD and to avoid premature implication of other genes in linkage disequilibrium.
Keywords: Base Sequence; Cysts; DNA, Intergenic; Evolution, Molecular; Exons; Glucosidases; Humans; Liver Diseases; Low Density Lipoprotein Receptor-Related Protein-5; Mutation

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability. - Santos-Cortez, Regie Lyn P; Khan, Valeed; Khan, Falak Sher; Mughal, Zaib-Un-Nisa; Chakchouk, Imen; Lee, Kwanghyuk; Rasheed, Memoona; Hamza, Rifat; Acharya, Anushree; Ullah, Ehsan; Saqib, Muhammad Arif Nadeem; Abbe, Izoduwa; et al. (Hum Genet, 2018)
Identification of Mendelian genes for neurodevelopmental disorders using exome sequencing to study autosomal recessive (AR) consanguineous pedigrees has been highly successful. To identify causal variants for syndromic and non-syndromic intellectual disability (ID), exome sequencing was performed using DNA samples from 22 consanguineous Pakistani families with ARID, of which 21 have additional phenotypes including microcephaly. To aid in variant identification, homozygosity mapping and linkage analysis were performed. DNA samples from affected family member(s) from every pedigree underwent exome sequencing. Identified rare damaging exome variants were tested for co-segregation with ID using Sanger sequencing. For seven ARID families, variants were identified in genes not previously associated with ID, including: EI24, FXR1 and TET3 for which knockout mouse models have brain defects; and CACNG7 and TRAPPC10 where cell studies suggest roles in important neural pathways. For two families, the novel ARID genes CARNMT1 and GARNL3 lie within previously reported ID microdeletion regions. We also observed homozygous variants in two ID candidate genes, GRAMD1B and TBRG1, for which each has been previously reported in a single family. An additional 14 families have homozygous variants in established ID genes, of which 11 variants are novel. All ARID genes have increased expression in specific structures of the developing and adult human brain and 91% of the genes are differentially expressed in utero or during early childhood. The identification of novel ARID candidate genes and variants adds to the knowledge base that is required to further understand human brain function and development.
Keywords: Adult; Consanguinity; Family; Female; Genes, Recessive; Genetic Markers; Humans; Intellectual Disability; Male; Middle Aged; Mutation; Neurodevelopmental Disorders; Pedigree

Novel digenic inheritance of PCDH15 and USH1G underlies profound non-syndromic hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Acharya, Anushree; Liaqat, Khurram; Nickerson, Deborah A; Bamshad, Michael J; Shah, Khadim; Ahmad, Wasim; Leal, Suzanne M (BMC Med Genet, 2018)
BACKGROUND: Digenic inheritance is the simplest model of oligenic disease. It can be observed when there is a strong epistatic interaction between two loci. For both syndromic and non-syndromic hearing impairment, several forms of digenic inheritance have been reported. METHODS: We performed exome sequencing in a Pakistani family with profound non-syndromic hereditary hearing impairment to identify the genetic cause of disease. RESULTS: We found that this family displays digenic inheritance for two trans heterozygous missense mutations, one in PCDH15 [p.(Arg1034His)] and another in USH1G [p.(Asp365Asn)]. Both of these genes are known to cause autosomal recessive non-syndromic hearing impairment and Usher syndrome. The protein products of PCDH15 and USH1G function together at the stereocilia tips in the hair cells and are necessary for proper mechanotransduction. Epistasis between Pcdh15 and Ush1G has been previously reported in digenic heterozygous mice. The digenic mice displayed a significant decrease in hearing compared to age-matched heterozygous animals. Until now no human examples have been reported. CONCLUSIONS: The discovery of novel digenic inheritance mechanisms in hereditary hearing impairment will aid in understanding the interaction between defective proteins and further define inner ear function and its interactome.
Keywords: Adult; Animals; Cadherins; Hearing Loss; Heterozygote; Humans; Male; Mechanotransduction, Cellular; Multifactorial Inheritance; Mutation; Nerve Tissue Proteins; Pakistan; Pedigree; Usher Syndromes; Young Adult

A novel homozygous variant in BMPR1B underlies acromesomelic dysplasia Hunter-Thompson type. - Ullah, Asmat; Umair, Muhammad; Muhammad, Dost; Bilal, Muhammad; Lee, Kwanghyuk; Leal, Suzanne M; Ahmad, Wasim (Ann Hum Genet, 2018)
Acromesomelic dysplasia is genetically heterogeneous group of skeletal disorders characterized by short stature and acromelia and mesomelia of limbs. Acromesomelic dysplasia segregates in an autosomal recessive pattern and is caused by biallelic sequence variants in three genes (NPR2, GDF5, and BMPR1B). A consanguineous family of Pakistani origin segregating a subtype of acromesomelic dysplasia called Hunter-Thompson was clinically and genetically evaluated. Genotyping of microsatellite markers and linkage analysis revealed a 7.78 Mb homozygous region on chromosome 4q22.3, which harbors BMPR1B. Sequence analysis of the gene revealed a novel homozygous missense variant (c.1190T > G, p.Met397Arg) that segregates with the disease phenotype within the family and produced a Logarithm of odds (LOD) score of 3.9 with the disease phenotype. This study reports on the first familial case of acromesomelic dysplasia Hunter-Thompson type. It is also the first report of BMPR1B underlying the etiology of acromesomelic dysplasia Hunter-Thompson type.

A novel NAA10 variant with impaired acetyltransferase activity causes developmental delay, intellectual disability, and hypertrophic cardiomyopathy. - Støve, Svein Isungset; Blenski, Marina; Stray-Pedersen, Asbjørg; Wierenga, Klaas J; Jhangiani, Shalini N; Akdemir, Zeynep Coban; Crawford, David; McTiernan, Nina; Myklebust, Line M; Purcarin, Gabriela; McNall-Knapp, Rene; Wadley, Alexandrea; et al. (Eur J Hum Genet, 2018)
The NAA10-NAA15 complex (NatA) is an N-terminal acetyltransferase that catalyzes N-terminal acetylation of ~40% of all human proteins. N-terminal acetylation has several different roles in the cell, including altering protein stability and degradation, protein localization and protein-protein interactions. In recent years several X-linked NAA10 variants have been associated with genetic disorders. We have identified a previously undescribed NAA10 c.215T>C p.(Ile72Thr) variant in three boys from two unrelated families with a milder phenotypic spectrum in comparison to most of the previously described patients with NAA10 variants. These boys have development delay, intellectual disability, and cardiac abnormalities as overlapping phenotypes. Functional studies reveal that NAA10 Ile72Thr is destabilized, while binding to NAA15 most likely is intact. Surprisingly, the NatA activity of NAA10 Ile72Thr appears normal while its monomeric activity is decreased. This study further broadens the phenotypic spectrum associated with NAA10 deficiency, and adds to the evidence that genotype-phenotype correlations for NAA10 variants are much more complex than initially anticipated.
Keywords: Cardiomyopathy, Hypertrophic; Child, Preschool; Developmental Disabilities; Enzyme Stability; HeLa Cells; Humans; Infant; Intellectual Disability; Male; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Phenotype; Protein Binding; Syndrome

A novel pathogenic variant in a family with paroxysmal kinesigenic dyskinesia and benign familial infantile seizures. - Lu, Jacqueline G; Bishop, Juliet; Cheyette, Sarah; Zhulin, Igor B; Guo, Su; Sobreira, Nara; Brenner, Steven E (Cold Spring Harb Mol Case Stud, 2018)
Paroxysmal kinesigenic dyskinesia (PKD) is a rare neurological disorder characterized by recurrent attacks of dyskinetic movements without alteration of consciousness that are often triggered by the initiation of voluntary movements. Whole-exome sequencing has revealed a cluster of pathogenic variants in (proline-rich transmembrane protein), a gene with a function in synaptic regulation that remains poorly understood. Here, we report the discovery of a novel pathogenic variant inherited in an autosomal dominant pattern in a family with PKD and benign familial infantile seizures (BFIS). After targeted Sanger sequencing did not identify the presence of previously described pathogenic variants, we carried out whole-exome sequencing in the proband and her affected paternal grandfather. This led to the discovery of a novel variant, NM_001256442:exon3:c.C959T/NP_660282.2:p.A320V, altering an evolutionarily conserved alanine at the amino acid position 320 located in the M2 transmembrane region. Sanger sequencing further confirmed the presence of this variant in four affected family members (paternal grandfather, father, brother, and proband) and its absence in two unaffected ones (paternal grandmother and mother). This newly found variant further reinforces the importance of in PKD, BFIS, and possibly other movement disorders. Future functional studies using animal models and human pluripotent stem cell models will provide new insights into the role of and the significance of this variant in regulating neural development and/or function.
Keywords: Amino Acid Sequence; Base Sequence; Child; Chromosome Segregation; Conserved Sequence; Dystonia; Epilepsy, Benign Neonatal; Evolution, Molecular; Family; Female; Humans; Infant; Inheritance Patterns; Male; Membrane Proteins; Mutation; Nerve Tissue Proteins; Pedigree

Novel STAT1 Gain-of-Function Mutation Presenting as Combined Immunodeficiency. - Hartono, Stella P; Vargas-Hernandez, Alexander; Ponsford, Mark J; Chinn, Ivan K; Jolles, Stephen; Wilson, Keith; Forbes, Lisa R (J Clin Immunol, 2018)

Peripheral Cone Dystrophy: Expanded Clinical Spectrum, Multimodal and Ultrawide-Field Imaging, and Genomic Analysis. - Sisk, Robert A; Hufnagel, Robert B; Laham, Ailee; Wohler, Elizabeth S; Sobreira, Nara; Ahmed, Zubair M (J Ophthalmol, 2018)
Purpose: To present new clinical features, multimodal and ultrawide-field imaging characteristics of peripheral cone dystrophy (PCD), and results of laboratory and genetic investigation to decipher the etiology. Methods: Retrospective observational case-series. Results: Three patients with PCD presented with bilateral paracentral scotomas and a mean visual acuity of 20/25. All exhibited confluent macular hyperautofluorescence with a central bull's eye lesion. Spectral-domain optical coherence tomography revealed loss of outer retinal elements, particularly the inner segment ellipsoid band and external limiting membrane, within the area of macular hyperautofluorescence. This area corresponded with a lightened fundus appearance and variable retinal pigment epithelium (RPE) abnormalities. Full field and multifocal electroretinography distinguished PCD from other photoreceptor dystrophies. Ultrawide-field imaging revealed irregular peripheral retinal lesions in a distribution greater nasally than temporally and not contiguous with the macular lesion. Functional and anatomic testing remained stable over a mean follow-up of 3 years. Laboratory investigation for causes of uveitis was negative. Whole exome sequencing identified rare variants in genes associated with macular or cone dystrophy or degeneration. Conclusions: In contrast to the original description, the funduscopic and fluorescein angiographic appearance of PCD is abnormal, although the defects are subtle. Peripheral lesions may be observed in some patients. Bilateral, symmetric, macular hyperautofluorescence associated with outer retinal atrophy that spares the fovea is a characteristic of PCD. Pathogenic variants in the same gene were not shared across the cohort, suggesting genetic heterogeneity. Further evaluation is warranted.

Perturbations of BMP/TGF-β and VEGF/VEGFR signalling pathways in non-syndromic sporadic brain arteriovenous malformations (BAVM). - Wang, Kun; Zhao, Sen; Liu, Bowen; Zhang, Qianqian; Li, Yaqi; Liu, Jiaqi; Shen, Yan; Ding, Xinghuan; Lin, Jiachen; Wu, Yong; Yan, Zihui; Chen, Jia; et al. (J Med Genet, 2018)
BACKGROUND: Brain arteriovenous malformations (BAVM) represent a congenital anomaly of the cerebral vessels with a prevalence of 10-18/100 000. BAVM is the leading aetiology of intracranial haemorrhage in children. Our objective was to identify gene variants potentially contributing to disease and to better define the molecular aetiology underlying non-syndromic sporadic BAVM. METHODS: We performed whole-exome trio sequencing of 100 unrelated families with a clinically uniform BAVM phenotype. Pathogenic variants were then studied in vivo using a transgenic zebrafish model. RESULTS: We identified four pathogenic heterozygous variants in four patients, including one in the established BAVM-related gene, , and three damaging variants in novel candidate genes: , and , which we then functionally validated in zebrafish. In addition, eight likely pathogenic heterozygous variants (, and ) were identified in eight patients, and 16 patients carried one or more variants of uncertain significance. Potential oligogenic inheritance ( with , with and with ) was identified in three patients. Regulation of sma- and mad-related proteins (SMADs) (involved in bone morphogenic protein (BMP)/transforming growth factor beta (TGF-β) signalling) and vascular endothelial growth factor (VEGF)/vascular endotheliual growth factor recepter 2 (VEGFR2) binding and activity (affecting the VEGF signalling pathway) were the most significantly affected biological process involved in the pathogenesis of BAVM. CONCLUSIONS: Our study highlights the specific role of BMP/TGF-β and VEGF/VEGFR signalling in the aetiology of BAVM and the efficiency of intensive parallel sequencing in the challenging context of genetically heterogeneous paradigm.

Phenotypic expansion illuminates multilocus pathogenic variation. - Karaca, Ender; Posey, Jennifer E; Coban Akdemir, Zeynep; Pehlivan, Davut; Harel, Tamar; Jhangiani, Shalini N; Bayram, Yavuz; Song, Xiaofei; Bahrambeigi, Vahid; Yuregir, Ozge Ozalp; Bozdogan, Sevcan; Yesil, Gözde; et al. (Genet Med, 2018)
PURPOSE: Multilocus variation-pathogenic variants in two or more disease genes-can potentially explain the underlying genetic basis for apparent phenotypic expansion in cases for which the observed clinical features extend beyond those reported in association with a "known" disease gene. METHODS: Analyses focused on 106 patients, 19 for whom apparent phenotypic expansion was previously attributed to variation at known disease genes. We performed a retrospective computational reanalysis of whole-exome sequencing data using stringent Variant Call File filtering criteria to determine whether molecular diagnoses involving additional disease loci might explain the observed expanded phenotypes. RESULTS: Multilocus variation was identified in 31.6% (6/19) of families with phenotypic expansion and 2.3% (2/87) without phenotypic expansion. Intrafamilial clinical variability within two families was explained by multilocus variation identified in the more severely affected sibling. CONCLUSION: Our findings underscore the role of multiple rare variants at different loci in the etiology of genetically and clinically heterogeneous cohorts. Intrafamilial phenotypic and genotypic variability allowed a dissection of genotype-phenotype relationships in two families. Our data emphasize the critical role of the clinician in diagnostic genomic analyses and demonstrate that apparent phenotypic expansion may represent blended phenotypes resulting from pathogenic variation at more than one locus.

Phenotypic expansion in - a common cause of intellectual disability in females. - Wang, Xia; Posey, Jennifer E; Rosenfeld, Jill A; Bacino, Carlos A; Scaglia, Fernando; Immken, LaDonna; Harris, Jill M; Hickey, Scott E; Mosher, Theresa M; Slavotinek, Anne; Zhang, Jing; Beuten, Joke; et al. (Ann Clin Transl Neurol, 2018)
De variants in account for 1-3% of unexplained intellectual disability (ID) cases and are amongst the most common causes of ID especially in females. Forty-seven patients (44 females, 3 males) have been described. We identified 31 additional individuals carrying 29 unique variants, including 30 postnatal individuals with complex clinical presentations of developmental delay or ID, and one fetus with abnormal ultrasound findings. Rare or novel phenotypes observed include respiratory problems, congenital heart disease, skeletal muscle mitochondrial DNA depletion, and late-onset neurologic decline. Our findings expand the spectrum of DNA variants and phenotypes associated with disorders.

The phenotypic spectrum of Xia-Gibbs syndrome. - Jiang, Yunyun; Wangler, Michael F; McGuire, Amy L; Lupski, James R; Posey, Jennifer E; Khayat, Michael M; Murdock, David R; Sanchez-Pulido, Luis; Ponting, Chris P; Xia, Fan; Hunter, Jill V; Meng, Qingchang; et al. (Am J Med Genet A, 2018)
Xia-Gibbs syndrome (XGS: OMIM # 615829) results from de novo truncating mutations within the AT-Hook DNA Binding Motif Containing 1 gene (AHDC1). To further define the phenotypic and molecular spectrum of this disorder, we established an XGS Registry and recruited patients from a worldwide pool of approximately 60 probands. Additional de novo truncating mutations were observed among 25 individuals, extending both the known number of mutation sites and the range of positions within the coding region that were sensitive to alteration. Detailed phenotypic examination of 20 of these patients via clinical records review and data collection from additional surveys showed a wider age range than previously described. Data from developmental milestones showed evidence for delayed speech and that males were more severely affected. Neuroimaging from six available patients showed an associated thinning of the corpus callosum and posterior fossa cysts. An increased risk of both scoliosis and seizures relative to the population burden was also observed. Data from a modified autism screening tool revealed that XGS shares significant overlap with autism spectrum disorders. These details of the phenotypic heterogeneity of XGS implicate specific genotype/phenotype correlations and suggest potential clinical management guidelines.

Plain-language medical vocabulary for precision diagnosis. - Vasilevsky, Nicole A; Foster, Erin D; Engelstad, Mark E; Carmody, Leigh; Might, Matt; Chambers, Chip; Dawkins, Hugh J S; Lewis, Janine; Della Rocca, Maria G; Snyder, Michelle; Boerkoel, Cornelius F; Rath, Ana; et al. (Nat Genet, 2018)

Predicting human genes susceptible to genomic instability associated with /-mediated rearrangements. - Song, Xiaofei; Beck, Christine R; Du, Renqian; Campbell, Ian M; Coban-Akdemir, Zeynep; Gu, Shen; Breman, Amy M; Stankiewicz, Pawel; Ira, Grzegorz; Shaw, Chad A; Lupski, James R (Genome Res, 2018)
elements, the short interspersed element numbering more than 1 million copies per human genome, can mediate the formation of copy number variants (CNVs) between substrate pairs. These /-mediated rearrangements (AAMRs) can result in pathogenic variants that cause diseases. To investigate the impact of AAMR on gene variation and human health, we first characterized s that are involved in mediating CNVs (CNV-s) and observed that these s tend to be evolutionarily younger. We then computationally generated, with the assistance of a supercomputer, a test data set consisting of 78 million pairs and predicted ∼18% of them are potentially susceptible to AAMR. We further determined the relative risk of AAMR in 12,074 OMIM genes using the count of predicted CNV- pairs and experimentally validated the predictions with 89 samples selected by correlating predicted hotspots with a database of CNVs identified by clinical chromosomal microarrays (CMAs) on the genomes of approximately 54,000 subjects. We fine-mapped 47 duplications, 40 deletions, and two complex rearrangements and examined a total of 52 breakpoint junctions of simple CNVs. Overall, 94% of the candidate breakpoints were at least partially mediated. We successfully predicted all (100%) of pairs that mediated deletions ( = 21) and achieved an 87% positive predictive value overall when including AAMR-generated deletions and duplications. We provided a tool, AluAluCNVpredictor, for assessing AAMR hotspots and their role in human disease. These results demonstrate the utility of our predictive model and provide insights into the genomic features and molecular mechanisms underlying AAMR.
Keywords: Alu Elements; DNA Copy Number Variations; Gene Duplication; Genome, Human; Genomic Instability; Humans; Sequence Deletion

A presynaptic congenital myasthenic syndrome attributed to a homozygous sequence variant in LAMA5. - Maselli, Ricardo A; Arredondo, Juan; Vázquez, Jessica; Chong, Jessica X; Bamshad, Michael J; Nickerson, Deborah A; Lara, Marian; Ng, Fiona; Lo, Victoria Lee; Pytel, Peter; McDonald, Craig M (Ann N Y Acad Sci, 2018)
We report a severe defect of neuromuscular transmission in a consanguineous patient with a homozygous variant in the laminin α5 subunit gene (LAMA5). The variant c.8046C > T (p.Arg2659Trp) is rare and has a predicted deleterious effect. The affected individual, who also carries a rare homozygous sequence variant in LAMA1, had normal cognitive function, but magnetic resonance brain imaging showed mild volume loss and periventricular T2 prolongation. Repetitive nerve stimulation at 2 Hz showed 50% decrement of compound muscle action potential amplitudes but 250% facilitation immediately after exercise, similar to that seen in Lambert-Eaton myasthenic syndrome. Endplate studies demonstrated a profound reduction of the endplate potential quantal content but normal amplitudes of miniature endplate potentials. Electron microscopy showed endplates with increased postsynaptic folding that were denuded or only partially occupied by small nerve terminals. Expression studies revealed that p.Arg2659Trp caused decreased binding of laminin α5 to SV2A and impaired laminin-521 cell adhesion and cell projection support in primary neuronal cultures. In summary, this report describing severe neuromuscular transmission failure in a patient with a LAMA5 mutation expands the list of phenotypes associated with defects in genes encoding α-laminins.
Keywords: Adult; Female; Humans; Lambert-Eaton Myasthenic Syndrome; Laminin; Motor Endplate; Myasthenic Syndromes, Congenital; Synaptic Transmission

Prioritization of Candidate Genes for Congenital Diaphragmatic Hernia in a Critical Region on Chromosome 4p16 using a Machine-Learning Algorithm. - Callaway, Danielle A; Campbell, Ian M; Stover, Samantha R; Hernandez-Garcia, Andres; Jhangiani, Shalini N; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Muzny, Donna; Lally, Kevin P; Lupski, James R; Shaw, Chad A; et al. (J Pediatr Genet, 2018)
Wolf-Hirschhorn syndrome (WHS) is caused by partial deletion of the short arm of chromosome 4 and is characterized by dysmorphic facies, congenital heart defects, intellectual/developmental disability, and increased risk for congenital diaphragmatic hernia (CDH). In this report, we describe a stillborn girl with WHS and a large CDH. A literature review revealed 15 cases of WHS with CDH, which overlap a 2.3-Mb CDH critical region. We applied a machine-learning algorithm that integrates large-scale genomic knowledge to genes within the 4p16.3 CDH critical region and identified , , , , , , , and as genes whose haploinsufficiency may contribute to the development of CDH.

Pro-inflammation Associated with a Gain-of-Function Mutation (R284S) in the Innate Immune Sensor STING. - Konno, Hiroyasu; Chinn, Ivan K; Hong, Diana; Orange, Jordan S; Lupski, James R; Mendoza, Alejandra; Pedroza, Luis A; Barber, Glen N (Cell Rep, 2018)
The cellular sensor stimulator of interferon genes (STING) initiates type I interferon (IFN) and cytokine production following association with cyclic dinucleotides (CDNs) generated from intracellular bacteria or via a cellular synthase, cGAS, after binding microbial or self-DNA. Although essential for protecting the host against infection, unscheduled STING signaling is now known to be responsible for a variety of autoinflammatory disorders. Here, we report a gain-of-function mutation in STING (R284S), isolated from a patient who did not require CDNs to augment activity and who manifested a constitutively active phenotype. Control of the Unc-51-like autophagy activating kinase 1 (ULK1) pathway, which has previously been shown to influence STING function, was potently able to suppress STING (R284S) activity to alleviate cytokine production. Our findings add to the growing list of inflammatory syndromes associated with spontaneous STING signaling and provide a therapeutic strategy for the treatment of STING-induced inflammatory disease.

Rhombencephalosynapsis: Fused cerebellum, confused geneticists. - Aldinger, Kimberly A; Dempsey, Jennifer C; Tully, Hannah M; Grout, Megan E; Mehaffey, Michele G; Dobyns, William B; Doherty, Dan (Am J Med Genet C Semin Med Genet, 2018)
Rhombencephalosynapsis (RES) is a unique cerebellar malformation characterized by fusion of the cerebellar hemispheres with partial or complete absence of a recognizable cerebellar vermis. Subsets of patients also have other brain malformations such as midbrain fusion with aqueductal stenosis, characteristic craniofacial features (prominent forehead, flat midface, hypertelorism, ear abnormalities), and somatic malformations (heart, kidney, spine, and limb defects). Similar to known genetic brain malformations, the RES cerebellar malformation is highly stereotyped, yet no genetic causes have been identified. Here, we outline our current understanding of the genetic basis for RES, discuss limitations, and outline future approaches to identifying the causes of this fascinating brain malformation.

The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin

Severe neurocognitive and growth disorders due to variation in THOC2, an essential component of nuclear mRNA export machinery. - Kumar, Raman; Gardner, Alison; Homan, Claire C; Douglas, Evelyn; Mefford, Heather; Wieczorek, Dagmar; Lüdecke, Hermann-Josef; Stark, Zornitza; Sadedin, Simon; Nowak, Catherine Bearce; Douglas, Jessica; Parsons, Gretchen; et al. (Hum Mutat, 2018)
Highly conserved TREX-mediated mRNA export is emerging as a key pathway in neuronal development and differentiation. TREX subunit variants cause neurodevelopmental disorders (NDDs) by interfering with mRNA export from the cell nucleus to the cytoplasm. Previously we implicated four missense variants in the X-linked THOC2 gene in intellectual disability (ID). We now report an additional six affected individuals from five unrelated families with two de novo and three maternally inherited pathogenic or likely pathogenic variants in THOC2 extending the genotypic and phenotypic spectrum. These comprise three rare missense THOC2 variants that affect evolutionarily conserved amino acid residues and reduce protein stability and two with canonical splice-site THOC2 variants that result in C-terminally truncated THOC2 proteins. We present detailed clinical assessment and functional studies on a de novo variant in a female with an epileptic encephalopathy and discuss an additional four families with rare variants in THOC2 with supportive evidence for pathogenicity. Severe neurocognitive features, including movement and seizure disorders, were observed in this cohort. Taken together our data show that even subtle alterations to the canonical molecular pathways such as mRNA export, otherwise essential for cellular life, can be compatible with life, but lead to NDDs in humans.

Somatic SLC35A2 variants in the brain are associated with intractable neocortical epilepsy. - Winawer, Melodie R; Griffin, Nicole G; Samanamud, Jorge; Baugh, Evan H; Rathakrishnan, Dinesh; Ramalingam, Senthilmurugan; Zagzag, David; Schevon, Catherine A; Dugan, Patricia; Hegde, Manu; Sheth, Sameer A; McKhann, Guy M; et al. (Ann Neurol, 2018)
OBJECTIVE: Somatic variants are a recognized cause of epilepsy-associated focal malformations of cortical development (MCD). We hypothesized that somatic variants may underlie a wider range of focal epilepsy, including nonlesional focal epilepsy (NLFE). Through genetic analysis of brain tissue, we evaluated the role of somatic variation in focal epilepsy with and without MCD. METHODS: We identified somatic variants through high-depth exome and ultra-high-depth candidate gene sequencing of DNA from epilepsy surgery specimens and leukocytes from 18 individuals with NLFE and 38 with focal MCD. RESULTS: We observed somatic variants in 5 cases in SLC35A2, a gene associated with glycosylation defects and rare X-linked epileptic encephalopathies. Nonsynonymous variants in SLC35A2 were detected in resected brain, and absent from leukocytes, in 3 of 18 individuals (17%) with NLFE, 1 female and 2 males, with variant allele frequencies (VAFs) in brain-derived DNA of 2 to 14%. Pathologic evaluation revealed focal cortical dysplasia type Ia (FCD1a) in 2 of the 3 NLFE cases. In the MCD cohort, nonsynonymous variants in SCL35A2 were detected in the brains of 2 males with intractable epilepsy, developmental delay, and magnetic resonance imaging suggesting FCD, with VAFs of 19 to 53%; Evidence for FCD was not observed in either brain tissue specimen. INTERPRETATION: We report somatic variants in SLC35A2 as an explanation for a substantial fraction of NLFE, a largely unexplained condition, as well as focal MCD, previously shown to result from somatic mutation but until now only in PI3K-AKT-mTOR pathway genes. Collectively, our findings suggest a larger role than previously recognized for glycosylation defects in the intractable epilepsies. Ann Neurol 2018.

STRetch: detecting and discovering pathogenic short tandem repeat expansions. - Dashnow, Harriet; Lek, Monkol; Phipson, Belinda; Halman, Andreas; Sadedin, Simon; Lonsdale, Andrew; Davis, Mark; Lamont, Phillipa; Clayton, Joshua S; Laing, Nigel G; MacArthur, Daniel G; Oshlack, Alicia (Genome Biol, 2018)
Short tandem repeat (STR) expansions have been identified as the causal DNA mutation in dozens of Mendelian diseases. Most existing tools for detecting STR variation with short reads do so within the read length and so are unable to detect the majority of pathogenic expansions. Here we present STRetch, a new genome-wide method to scan for STR expansions at all loci across the human genome. We demonstrate the use of STRetch for detecting STR expansions using short-read whole-genome sequencing data at known pathogenic loci as well as novel STR loci. STRetch is open source software, available from github.com/Oshlack/STRetch .
Keywords: Alleles; Chromosomes, Human; DNA Repeat Expansion; Genetic Loci; Genome, Human; Humans; Microsatellite Repeats; Polymerase Chain Reaction; Software

SYT1-associated neurodevelopmental disorder: a case series. - Baker, Kate; Gordon, Sarah L; Melland, Holly; Bumbak, Fabian; Scott, Daniel J; Jiang, Tess J; Owen, David; Turner, Bradley J; Boyd, Stewart G; Rossi, Mari; Al-Raqad, Mohammed; Elpeleg, Orly; et al. (Brain, 2018)
Synaptotagmin 1 (SYT1) is a critical mediator of fast, synchronous, calcium-dependent neurotransmitter release and also modulates synaptic vesicle endocytosis. This paper describes 11 patients with de novo heterozygous missense mutations in SYT1. All mutations alter highly conserved residues, and cluster in two regions of the SYT1 C2B domain at positions Met303 (M303K), Asp304 (D304G), Asp366 (D366E), Ile368 (I368T) and Asn371 (N371K). Phenotypic features include infantile hypotonia, congenital ophthalmic abnormalities, childhood-onset hyperkinetic movement disorders, motor stereotypies, and developmental delay varying in severity from moderate to profound. Behavioural characteristics include sleep disturbance and episodic agitation. Absence of epileptic seizures and normal orbitofrontal head circumference are important negative features. Structural MRI is unremarkable but EEG disturbance is universal, characterized by intermittent low frequency high amplitude oscillations. The functional impact of these five de novo SYT1 mutations has been assessed by expressing rat SYT1 protein containing the equivalent human variants in wild-type mouse primary hippocampal cultures. All mutant forms of SYT1 were expressed at levels approximately equal to endogenous wild-type protein, and correctly localized to nerve terminals at rest, except for SYT1M303K, which was expressed at a lower level and failed to localize at nerve terminals. Following stimulation, SYT1I368T and SYT1N371K relocalized to nerve terminals at least as efficiently as wild-type SYT1. However, SYT1D304G and SYT1D366E failed to relocalize to nerve terminals following stimulation, indicative of impairments in endocytic retrieval and trafficking of SYT1. In addition, the presence of SYT1 variants at nerve terminals induced a slowing of exocytic rate following sustained action potential stimulation. The extent of disturbance to synaptic vesicle kinetics is mirrored by the severity of the affected individuals' phenotypes, suggesting that the efficiency of SYT1-mediated neurotransmitter release is critical to cognitive development. In summary, de novo dominant SYT1 missense mutations are associated with a recognizable neurodevelopmental syndrome, and further cases can now be diagnosed based on clinical features, electrophysiological signature and mutation characteristics. Variation in phenotype severity may reflect mutation-specific impact on the diverse physiological functions of SYT1.

Truncating Variants in NAA15 Are Associated with Variable Levels of Intellectual Disability, Autism Spectrum Disorder, and Congenital Anomalies. - Cheng, Hanyin; Dharmadhikari, Avinash V; Varland, Sylvia; Ma, Ning; Domingo, Deepti; Kleyner, Robert; Rope, Alan F; Yoon, Margaret; Stray-Pedersen, Asbjørg; Posey, Jennifer E; Crews, Sarah R; Eldomery, Mohammad K; et al. (Am J Hum Genet, 2018)
N-alpha-acetylation is a common co-translational protein modification that is essential for normal cell function in humans. We previously identified the genetic basis of an X-linked infantile lethal Mendelian disorder involving a c.109T>C (p.Ser37Pro) missense variant in NAA10, which encodes the catalytic subunit of the N-terminal acetyltransferase A (NatA) complex. The auxiliary subunit of the NatA complex, NAA15, is the dimeric binding partner for NAA10. Through a genotype-first approach with whole-exome or genome sequencing (WES/WGS) and targeted sequencing analysis, we identified and phenotypically characterized 38 individuals from 33 unrelated families with 25 different de novo or inherited, dominantly acting likely gene disrupting (LGD) variants in NAA15. Clinical features of affected individuals with LGD variants in NAA15 include variable levels of intellectual disability, delayed speech and motor milestones, and autism spectrum disorder. Additionally, mild craniofacial dysmorphology, congenital cardiac anomalies, and seizures are present in some subjects. RNA analysis in cell lines from two individuals showed degradation of the transcripts with LGD variants, probably as a result of nonsense-mediated decay. Functional assays in yeast confirmed a deleterious effect for two of the LGD variants in NAA15. Further supporting a mechanism of haploinsufficiency, individuals with copy-number variant (CNV) deletions involving NAA15 and surrounding genes can present with mild intellectual disability, mild dysmorphic features, motor delays, and decreased growth. We propose that defects in NatA-mediated N-terminal acetylation (NTA) lead to variable levels of neurodevelopmental disorders in humans, supporting the importance of the NatA complex in normal human development.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Autism Spectrum Disorder; Cell Line; Child; Exons; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Genetic Variation; Humans; Intellectual Disability; Male; Middle Aged; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Pedigree; Phenotype; RNA, Messenger; Saccharomyces cerevisiae

Tuberculosis and impaired IL-23-dependent IFN-γ immunity in humans homozygous for a common missense variant. - Boisson-Dupuis, Stéphanie; Ramirez-Alejo, Noe; Li, Zhi; Patin, Etienne; Rao, Geetha; Kerner, Gaspard; Lim, Che Kang; Krementsov, Dimitry N; Hernandez, Nicholas; Ma, Cindy S; Zhang, Qian; Markle, Janet; et al. (Sci Immunol, 2018)
Inherited IL-12Rβ1 and TYK2 deficiencies impair both IL-12- and IL-23-dependent IFN-γ immunity and are rare monogenic causes of tuberculosis, each found in less than 1/600,000 individuals. We show that homozygosity for the common P1104A allele, which is found in about 1/600 Europeans and between 1/1000 and 1/10,000 individuals in regions other than East Asia, is more frequent in a cohort of patients with tuberculosis from endemic areas than in ethnicity-adjusted controls ( = 8.37 × 10; odds ratio, 89.31; 95% CI, 14.7 to 1725). Moreover, the frequency of P1104A in Europeans has decreased, from about 9% to 4.2%, over the past 4000 years, consistent with purging of this variant by endemic tuberculosis. Surprisingly, we also show that TYK2 P1104A impairs cellular responses to IL-23, but not to IFN-α, IL-10, or even IL-12, which, like IL-23, induces IFN-γ via activation of TYK2 and JAK2. Moreover, TYK2 P1104A is properly docked on cytokine receptors and can be phosphorylated by the proximal JAK, but lacks catalytic activity. Last, we show that the catalytic activity of TYK2 is essential for IL-23, but not IL-12, responses in cells expressing wild-type JAK2. In contrast, the catalytic activity of JAK2 is redundant for both IL-12 and IL-23 responses, because the catalytically inactive P1057A JAK2, which is also docked and phosphorylated, rescues signaling in cells expressing wild-type TYK2. In conclusion, homozygosity for the catalytically inactive P1104A missense variant of selectively disrupts the induction of IFN-γ by IL-23 and is a common monogenic etiology of tuberculosis.

A variant in LMX1A causes autosomal recessive severe-to-profound hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Liaqat, Khurram; Jan, Abid; Nasir, Abdul; Hussain, Shabir; Nickerson, Deborah A; Bamshad, Michael J; Ullah, Asmat; Ahmad, Wasim; Leal, Suzanne M (Hum Genet, 2018)
Hereditary hearing impairment is a common sensory disorder that is genetically and phenotypically heterogeneous. In this study, we used a homozygosity mapping and exome sequencing strategy to study a consanguineous Pakistani family with autosomal recessive severe-to-profound hearing impairment. This led to the identification of a missense variant (p.Ile369Thr) in the LMX1A gene affecting a conserved residue in the C-terminus of the protein, which was predicted damaging by an in silico bioinformatics analysis. The p.Ile369Thr variant disrupts several C-terminal and homeodomain residue interactions, including an interaction with homeodomain residue p.Val241 that was previously found to be involved in autosomal dominant progressive HI. LIM-homeodomain factor Lmx1a is expressed in the inner ear through development, shows a progressive restriction to non-sensory epithelia, and is important in the separation of the sensory and non-sensory domains in the inner ear. Homozygous Lmx1a mutant mice (Dreher) are deaf with dysmorphic ears with an abnormal morphogenesis and fused and misshapen sensory organs; however, computed tomography performed on a hearing-impaired family member did not reveal any cochleovestibular malformations. Our results suggest that LMX1A is involved in both human autosomal recessive and dominant sensorineural hearing impairment.
Keywords: Adolescent; Adult; Animals; Child; Disease Models, Animal; Ear, Inner; Female; Genes, Dominant; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; LIM-Homeodomain Proteins; Male; Mice; Mutation, Missense; Pedigree; Transcription Factors; Whole Exome Sequencing

Variants in EXOSC9 Disrupt the RNA Exosome and Result in Cerebellar Atrophy with Spinal Motor Neuronopathy. - Burns, David T; Donkervoort, Sandra; Müller, Juliane S; Knierim, Ellen; Bharucha-Goebel, Diana; Faqeih, Eissa Ali; Bell, Stephanie K; AlFaifi, Abdullah Y; Monies, Dorota; Millan, Francisca; Retterer, Kyle; Dyack, Sarah; et al. (Am J Hum Genet, 2018)
The exosome is a conserved multi-protein complex that is essential for correct RNA processing. Recessive variants in exosome components EXOSC3, EXOSC8, and RBM7 cause various constellations of pontocerebellar hypoplasia (PCH), spinal muscular atrophy (SMA), and central nervous system demyelination. Here, we report on four unrelated affected individuals with recessive variants in EXOSC9 and the effect of the variants on the function of the RNA exosome in vitro in affected individuals' fibroblasts and skeletal muscle and in vivo in zebrafish. The clinical presentation was severe, early-onset, progressive SMA-like motor neuronopathy, cerebellar atrophy, and in one affected individual, congenital fractures of the long bones. Three affected individuals of different ethnicity carried the homozygous c.41T>C (p.Leu14Pro) variant, whereas one affected individual was compound heterozygous for c.41T>C (p.Leu14Pro) and c.481C>T (p.Arg161). We detected reduced EXOSC9 in fibroblasts and skeletal muscle and observed a reduction of the whole multi-subunit exosome complex on blue-native polyacrylamide gel electrophoresis. RNA sequencing of fibroblasts and skeletal muscle detected significant >2-fold changes in genes involved in neuronal development and cerebellar and motor neuron degeneration, demonstrating the widespread effect of the variants. Morpholino oligonucleotide knockdown and CRISPR/Cas9-mediated mutagenesis of exosc9 in zebrafish recapitulated aspects of the human phenotype, as they have in other zebrafish models of exosomal disease. Specifically, portions of the cerebellum and hindbrain were absent, and motor neurons failed to develop and migrate properly. In summary, we show that variants in EXOSC9 result in a neurological syndrome combining cerebellar atrophy and spinal motoneuronopathy, thus expanding the list of human exosomopathies.
Keywords: Amino Acid Sequence; Animals; Atrophy; Base Sequence; Cerebellum; Child, Preschool; Exosome Multienzyme Ribonuclease Complex; Exosomes; Female; Fibroblasts; Gene Knockdown Techniques; Genetic Variation; Haplotypes; Humans; Infant; Male; Motor Neurons; Muscle, Skeletal; Pedigree; RNA-Binding Proteins; Spinal Cord; Zebrafish

Whole exome sequencing analysis in severe chronic obstructive pulmonary disease. - Qiao, Dandi; Ameli, Asher; Prokopenko, Dmitry; Chen, Han; Kho, Alvin T; Parker, Margaret M; Morrow, Jarrett; Hobbs, Brian D; Liu, Yanhong; Beaty, Terri H; Crapo, James D; Barnes, Kathleen C; et al. (Hum Mol Genet, 2018)
Chronic obstructive pulmonary disease (COPD), one of the leading causes of death worldwide, is substantially influenced by genetic factors. Alpha-1 antitrypsin deficiency demonstrates that rare coding variants of large effect can influence COPD susceptibility. To identify additional rare coding variants in patients with severe COPD, we conducted whole exome sequencing analysis in 2543 subjects from two family-based studies (Boston Early-Onset COPD Study and International COPD Genetics Network) and one case-control study (COPDGene). Applying a gene-based segregation test in the family-based data, we identified significant segregation of rare loss of function variants in TBC1D10A and RFPL1 (P-value < 2x10-6), but were unable to find similar variants in the case-control study. In single-variant, gene-based and pathway association analyses, we were unable to find significant findings that replicated or were significant in meta-analysis. However, we found that the top results in the two datasets were in proximity to each other in the protein-protein interaction network (P-value = 0.014), suggesting enrichment of these results for similar biological processes. A network of these association results and their neighbors was significantly enriched in the transforming growth factor beta-receptor binding and cilia-related pathways. Finally, in a more detailed examination of candidate genes, we identified individuals with putative high-risk variants, including patients harboring homozygous mutations in genes associated with cutis laxa and Niemann-Pick Disease Type C. Our results likely reflect heterogeneity of genetic risk for COPD along with limitations of statistical power and functional annotation, and highlight the potential of network analysis to gain insight into genetic association studies.
Keywords: Adolescent; Adult; Aged; Case-Control Studies; DNA Mutational Analysis; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Whole Exome Sequencing; Young Adult

Whole exome sequencing frequently detects a monogenic cause in early onset nephrolithiasis and nephrocalcinosis. - Daga, Ankana; Majmundar, Amar J; Braun, Daniela A; Gee, Heon Yung; Lawson, Jennifer A; Shril, Shirlee; Jobst-Schwan, Tilman; Vivante, Asaf; Schapiro, David; Tan, Weizhen; Warejko, Jillian K; Widmeier, Eugen; et al. (Kidney Int, 2018)
The incidence of nephrolithiasis continues to rise. Previously, we showed that a monogenic cause could be detected in 11.4% of individuals with adult-onset nephrolithiasis or nephrocalcinosis and in 16.7-20.8% of individuals with onset before 18 years of age, using gene panel sequencing of 30 genes known to cause nephrolithiasis/nephrocalcinosis. To overcome the limitations of panel sequencing, we utilized whole exome sequencing in 51 families, who presented before age 25 years with at least one renal stone or with a renal ultrasound finding of nephrocalcinosis to identify the underlying molecular genetic cause of disease. In 15 of 51 families, we detected a monogenic causative mutation by whole exome sequencing. A mutation in seven recessive genes (AGXT, ATP6V1B1, CLDN16, CLDN19, GRHPR, SLC3A1, SLC12A1), in one dominant gene (SLC9A3R1), and in one gene (SLC34A1) with both recessive and dominant inheritance was detected. Seven of the 19 different mutations were not previously described as disease-causing. In one family, a causative mutation in one of 117 genes that may represent phenocopies of nephrolithiasis-causing genes was detected. In nine of 15 families, the genetic diagnosis may have specific implications for stone management and prevention. Several factors that correlated with the higher detection rate in our cohort were younger age at onset of nephrolithiasis/nephrocalcinosis, presence of multiple affected members in a family, and presence of consanguinity. Thus, we established whole exome sequencing as an efficient approach toward a molecular genetic diagnosis in individuals with nephrolithiasis/nephrocalcinosis who manifest before age 25 years.
Keywords: Adolescent; Age of Onset; Child; Child, Preschool; Disease Progression; Female; Genetic Association Studies; Genetic Markers; Genetic Predisposition to Disease; Heredity; Humans; Infant; Male; Mutation; Nephrocalcinosis; Nephrolithiasis; Pedigree; Phenotype; Predictive Value of Tests; Prognosis; Risk Factors; Tomography, X-Ray Computed; Ultrasonography; Whole Exome Sequencing; Young Adult

Whole Exome Sequencing of Patients with Steroid-Resistant Nephrotic Syndrome. - Warejko, Jillian K; Tan, Weizhen; Daga, Ankana; Schapiro, David; Lawson, Jennifer A; Shril, Shirlee; Lovric, Svjetlana; Ashraf, Shazia; Rao, Jia; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; et al. (Clin J Am Soc Nephrol, 2018)
BACKGROUND AND OBJECTIVES: Steroid-resistant nephrotic syndrome overwhelmingly progresses to ESRD. More than 30 monogenic genes have been identified to cause steroid-resistant nephrotic syndrome. We previously detected causative mutations using targeted panel sequencing in 30% of patients with steroid-resistant nephrotic syndrome. Panel sequencing has a number of limitations when compared with whole exome sequencing. We employed whole exome sequencing to detect monogenic causes of steroid-resistant nephrotic syndrome in an international cohort of 300 families. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Three hundred thirty-five individuals with steroid-resistant nephrotic syndrome from 300 families were recruited from April of 1998 to June of 2016. Age of onset was restricted to <25 years of age. Exome data were evaluated for 33 known monogenic steroid-resistant nephrotic syndrome genes. RESULTS: In 74 of 300 families (25%), we identified a causative mutation in one of 20 genes known to cause steroid-resistant nephrotic syndrome. In 11 families (3.7%), we detected a mutation in a gene that causes a phenocopy of steroid-resistant nephrotic syndrome. This is consistent with our previously published identification of mutations using a panel approach. We detected a causative mutation in a known steroid-resistant nephrotic syndrome gene in 38% of consanguineous families and in 13% of nonconsanguineous families, and 48% of children with congenital nephrotic syndrome. A total of 68 different mutations were detected in 20 of 33 steroid-resistant nephrotic syndrome genes. Fifteen of these mutations were novel. , , , and were the most common genes in which we detected a mutation. In another 28% of families, we detected mutations in one or more candidate genes for steroid-resistant nephrotic syndrome. CONCLUSIONS: Whole exome sequencing is a sensitive approach toward diagnosis of monogenic causes of steroid-resistant nephrotic syndrome. A molecular genetic diagnosis of steroid-resistant nephrotic syndrome may have important consequences for the management of treatment and kidney transplantation in steroid-resistant nephrotic syndrome.

Whole Exome Sequencing Reveals a Monogenic Cause of Disease in ≈43% of 35 Families With Midaortic Syndrome. - Warejko, Jillian K; Schueler, Markus; Vivante, Asaf; Tan, Weizhen; Daga, Ankana; Lawson, Jennifer A; Braun, Daniela A; Shril, Shirlee; Amann, Kassaundra; Somers, Michael J G; Rodig, Nancy M; Baum, Michelle A; et al. (Hypertension, 2018)
Midaortic syndrome (MAS) is a rare cause of severe childhood hypertension characterized by narrowing of the abdominal aorta in children and is associated with extensive vascular disease. It may occur as part of a genetic syndrome, such as neurofibromatosis, or as consequence of a pathological inflammatory disease. However, most cases are considered idiopathic. We hypothesized that in a high percentage of these patients, a monogenic cause of disease may be detected by evaluating whole exome sequencing data for mutations in 1 of 38 candidate genes previously described to cause vasculopathy. We studied a cohort of 36 individuals from 35 different families with MAS by exome sequencing. In 15 of 35 families (42.9%), we detected likely causal dominant mutations. In 15 of 35 (42.9%) families with MAS, whole exome sequencing revealed a mutation in one of the genes previously associated with vascular disease (, , , , and ). Ten of the 15 mutations have not previously been reported. This is the first report of , , or mutations in individuals with MAS. Mutations were detected in (6/15 families), (4/15 families), (3/15 families), and one family each for and Eight individuals had syndromic disease and 7 individuals had isolated MAS. Whole exome sequencing can provide conclusive molecular genetic diagnosis in a high fraction of individuals with syndromic or isolated MAS. Establishing an etiologic diagnosis may reveal genotype/phenotype correlations for MAS in the future and should, therefore, be performed routinely in MAS.
Keywords: Adolescent; Aorta, Abdominal; Aortic Valve Stenosis; Child; Child, Preschool; Cohort Studies; Female; Genetic Association Studies; Humans; Hypertension; Jagged-1 Protein; Male; Mutation; Neurofibromatoses; Neurofibromin 1; Pedigree; Syndrome; United States; Whole Exome Sequencing

Whole-Exome Sequencing Identifies Causative Mutations in Families with Congenital Anomalies of the Kidney and Urinary Tract. - van der Ven, Amelie T; Connaughton, Dervla M; Ityel, Hadas; Mann, Nina; Nakayama, Makiko; Chen, Jing; Vivante, Asaf; Hwang, Daw-Yang; Schulz, Julian; Braun, Daniela A; Schmidt, Johanna Magdalena; Schapiro, David; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Congenital anomalies of the kidney and urinary tract (CAKUT) are the most prevalent cause of kidney disease in the first three decades of life. Previous gene panel studies showed monogenic causation in up to 12% of patients with CAKUT. METHODS: We applied whole-exome sequencing to analyze the genotypes of individuals from 232 families with CAKUT, evaluating for mutations in single genes known to cause human CAKUT and genes known to cause CAKUT in mice. In consanguineous or multiplex families, we additionally performed a search for novel monogenic causes of CAKUT. RESULTS: In 29 families (13%), we detected a causative mutation in a known gene for isolated or syndromic CAKUT that sufficiently explained the patient's CAKUT phenotype. In three families (1%), we detected a mutation in a gene reported to cause a phenocopy of CAKUT. In 15 of 155 families with isolated CAKUT, we detected deleterious mutations in syndromic CAKUT genes. Our additional search for novel monogenic causes of CAKUT in consanguineous and multiplex families revealed a potential single, novel monogenic CAKUT gene in 19 of 232 families (8%). CONCLUSIONS: We identified monogenic mutations in a known human CAKUT gene or CAKUT phenocopy gene as the cause of disease in 14% of the CAKUT families in this study. Whole-exome sequencing provides an etiologic diagnosis in a high fraction of patients with CAKUT and will provide a new basis for the mechanistic understanding of CAKUT.

Whole-exome sequencing identifies mutations in in a mild form of Carey-Fineman-Ziter syndrome. - Alrohaif, Hadil; Topf, Ana; Evangelista, Teresinha; Lek, Monkol; McArthur, Daniel; Lochmüller, Hanns (Neurol Genet, 2018)

Whole-Exome Sequencing Identifies Novel Variants for Tooth Agenesis. - Dinckan, N; Du, R; Petty, L E; Coban-Akdemir, Z; Jhangiani, S N; Paine, I; Baugh, E H; Erdem, A P; Kayserili, H; Doddapaneni, H; Hu, J; Muzny, D M; et al. (J Dent Res, 2018)
Tooth agenesis is a common craniofacial abnormality in humans and represents failure to develop 1 or more permanent teeth. Tooth agenesis is complex, and variations in about a dozen genes have been reported as contributing to the etiology. Here, we combined whole-exome sequencing, array-based genotyping, and linkage analysis to identify putative pathogenic variants in candidate disease genes for tooth agenesis in 10 multiplex Turkish families. Novel homozygous and heterozygous variants in LRP6, DKK1, LAMA3, and COL17A1 genes, as well as known variants in WNT10A, were identified as likely pathogenic in isolated tooth agenesis. Novel variants in KREMEN1 were identified as likely pathogenic in 2 families with suspected syndromic tooth agenesis. Variants in more than 1 gene were identified segregating with tooth agenesis in 2 families, suggesting oligogenic inheritance. Structural modeling of missense variants suggests deleterious effects to the encoded proteins. Functional analysis of an indel variant (c.3607+3_6del) in LRP6 suggested that the predicted resulting mRNA is subject to nonsense-mediated decay. Our results support a major role for WNT pathways genes in the etiology of tooth agenesis while revealing new candidate genes. Moreover, oligogenic cosegregation was suggestive for complex inheritance and potentially complex gene product interactions during development, contributing to improved understanding of the genetic etiology of familial tooth agenesis.
Keywords: Anodontia; Female; Genetic Linkage; Genetic Variation; Humans; Intercellular Signaling Peptides and Proteins; Laminin; Low Density Lipoprotein Receptor-Related Protein-6; Male; Membrane Proteins; Mutation, Missense; Pedigree; Real-Time Polymerase Chain Reaction; Turkey; Whole Exome Sequencing; Wnt Proteins

WNT Signaling Perturbations Underlie the Genetic Heterogeneity of Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Coban-Akdemir, Zeynep; Bayram, Yavuz; Bahrambeigi, Vahid; Hoischen, Alexander; van Bon, Bregje W M; Gezdirici, Alper; Gulec, Elif Yilmaz; Ramond, Francis; Touraine, Renaud; Thevenon, Julien; et al. (Am J Hum Genet, 2018)
Locus heterogeneity characterizes a variety of skeletal dysplasias often due to interacting or overlapping signaling pathways. Robinow syndrome is a skeletal disorder historically refractory to molecular diagnosis, potentially stemming from substantial genetic heterogeneity. All current known pathogenic variants reside in genes within the noncanonical Wnt signaling pathway including ROR2, WNT5A, and more recently, DVL1 and DVL3. However, ∼70% of autosomal-dominant Robinow syndrome cases remain molecularly unsolved. To investigate this missing heritability, we recruited 21 families with at least one family member clinically diagnosed with Robinow or Robinow-like phenotypes and performed genetic and genomic studies. In total, four families with variants in FZD2 were identified as well as three individuals from two families with biallelic variants in NXN that co-segregate with the phenotype. Importantly, both FZD2 and NXN are relevant protein partners in the WNT5A interactome, supporting their role in skeletal development. In addition to confirming that clustered -1 frameshifting variants in DVL1 and DVL3 are the main contributors to dominant Robinow syndrome, we also found likely pathogenic variants in candidate genes GPC4 and RAC3, both linked to the Wnt signaling pathway. These data support an initial hypothesis that Robinow syndrome results from perturbation of the Wnt/PCP pathway, suggest specific relevant domains of the proteins involved, and reveal key contributors in this signaling cascade during human embryonic development. Contrary to the view that non-allelic genetic heterogeneity hampers gene discovery, this study demonstrates the utility of rare disease genomic studies to parse gene function in human developmental pathways.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Chromosome Segregation; Craniofacial Abnormalities; Diagnosis, Differential; Dwarfism; Female; Genes, Dominant; Genetic Association Studies; Genetic Heterogeneity; Humans; Limb Deformities, Congenital; Male; Middle Aged; Mutation, Missense; Phenotype; Urogenital Abnormalities; Wnt Signaling Pathway

Ximmer: a system for improving accuracy and consistency of CNV calling from exome data. - Sadedin, Simon P; Ellis, Justine A; Masters, Seth L; Oshlack, Alicia (Gigascience, 2018)
Background: While exome and targeted next-generation DNA sequencing are primarily used for detecting single nucleotide changes and small indels, detection of copy number variants (CNVs) can provide highly valuable additional information from the data. Although there are dozens of exome CNV detection methods available, these are often difficult to use, and accuracy varies unpredictably between and within datasets. Findings: We present Ximmer, a tool that supports an end-to-end process for evaluating, tuning, and running analysis methods for detection of CNVs in germline samples. Ximmer includes a simulation framework, implementations of several commonly used CNV detection methods, and a visualization and curation tool that together enable interactive exploration and quality control of CNV results. Using Ximmer, we comprehensively evaluate CNV detection on four datasets using five different detection methods. We show that application of Ximmer can improve accuracy and aid in quality control of CNV detection results. In addition, Ximmer can be used to run analyses and explore CNV results in exome data. Conclusions: Ximmer offers a comprehensive tool and method for applying and improving accuracy of CNV detection methods for exome data.
Keywords: Algorithms; Computational Biology; Computer Simulation; DNA Copy Number Variations; Exome; High-Throughput Nucleotide Sequencing; Humans; Reproducibility of Results; ROC Curve; Sensitivity and Specificity; Software

Xq26.3 Duplication in a Boy With Motor Delay and Low Muscle Tone Refines the X-Linked Acrogigantism Genetic Locus. - Trivellin, Giampaolo; Sharwood, Erin; Hijazi, Hadia; Carvalho, Claudia M B; Yuan, Bo; Tatton-Brown, Katrina; Coman, David; Lupski, James R; Cotterill, Andrew M; Lodish, Maya B; Stratakis, Constantine A (J Endocr Soc, 2018)
We describe a 4-year-old boy with developmental delay who was found to carry by clinical grade (CG) molecular cytogenetics (MCs) a chromosome Xq26 microduplication. The report prompted a referral of the patient for possible X-linked acrogigantism (X-LAG), a well-defined condition (MIM300942) due to chromosomal microduplication of a nearby region. The patient was evaluated clinically and investigated for endocrine abnormalities related to X-LAG and not only did he not have acrogigantism, but his growth parameters and other hormones were all normal. We then performed high definition MCs and the duplication copy number variant (CNV) was confirmed to precisely map outside the X-LAG critical region and definitely did not harbor the X-LAG candidate gene, . The patient's phenotype resembled that of other patients with Xq26 CNVs. The case is instructive for the need for high definition MCs when CG MCs' results are inconsistent with the patient's phenotype. It is also useful for further supporting the contention that is the gene responsible for X-LAG.

22q11.2q13 duplication including SOX10 causes sex-reversal and peripheral demyelinating neuropathy, central dysmyelinating leukodystrophy, Waardenburg syndrome, and Hirschsprung disease. - Falah, Nadia; Posey, Jennifer E; Thorson, Willa; Benke, Paul; Tekin, Mustafa; Tarshish, Brocha; Lupski, James R; Harel, Tamar (Am J Med Genet A, 2017)
Diagnosis of genetic syndromes may be difficult when specific components of a disorder manifest at a later age. We present a follow up of a previous report [Seeherunvong et al., (2004); AJMGA 127: 149-151], of an individual with 22q duplication and sex-reversal syndrome. The subject's phenotype evolved to include peripheral and central demyelination, Waardenburg syndrome type IV, and Hirschsprung disease (PCWH; MIM 609136). DNA microarray analysis defined the duplication at 22q11.2q13, including SOX10. Sequencing of the coding region of SOX10 did not reveal any mutations. Our data suggest that SOX10 duplication can cause disorders of sex development and PCWH, supporting the hypothesis that SOX10 toxic gain of function rather than dominant negative activity underlies PCWH.
Keywords: 46, XX Testicular Disorders of Sex Development; African Americans; Chromosome Duplication; Chromosomes, Human, Pair 22; Demyelinating Diseases; Hirschsprung Disease; Humans; Kidney Failure, Chronic; Male; Pelizaeus-Merzbacher Disease; SOXE Transcription Factors; Waardenburg Syndrome

Activation of a cryptic splice site in the mitochondrial elongation factor GFM1 causes combined OXPHOS deficiency. - Simon, Mariella T; Ng, Bobby G; Friederich, Marisa W; Wang, Raymond Y; Boyer, Monica; Kircher, Martin; Collard, Renata; Buckingham, Kati J; Chang, Richard; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; et al. (Mitochondrion, 2017)
We report the clinical, biochemical, and molecular findings in two brothers with encephalopathy and multi-systemic disease. Abnormal transferrin glycoforms were suggestive of a type I congenital disorder of glycosylation (CDG). While exome sequencing was negative for CDG related candidate genes, the testing revealed compound heterozygous mutations in the mitochondrial elongation factor G gene (GFM1). One of the mutations had been reported previously while the second, novel variant was found deep in intron 6, activating a cryptic splice site. Functional studies demonstrated decreased GFM1 protein levels, suggested disrupted assembly of mitochondrial complexes III and V and decreased activities of mitochondrial complexes I and IV, all indicating combined OXPHOS deficiency.
Keywords: Child; Child, Preschool; Congenital Abnormalities; Gene Expression; Humans; Infant; Infant, Newborn; Male; Mitochondrial Proteins; Oxidative Phosphorylation; Peptide Elongation Factor G; RNA Splice Sites

Advillin acts upstream of phospholipase C ϵ1 in steroid-resistant nephrotic syndrome. - Rao, Jia; Ashraf, Shazia; Tan, Weizhen; van der Ven, Amelie T; Gee, Heon Yung; Braun, Daniela A; Fehér, Krisztina; George, Sudeep P; Esmaeilniakooshkghazi, Amin; Choi, Won-Il; Jobst-Schwan, Tilman; Schneider, Ronen; et al. (J Clin Invest, 2017)
Steroid-resistant nephrotic syndrome (SRNS) is a frequent cause of chronic kidney disease. Here, we identified recessive mutations in the gene encoding the actin-binding protein advillin (AVIL) in 3 unrelated families with SRNS. While all AVIL mutations resulted in a marked loss of its actin-bundling ability, truncation of AVIL also disrupted colocalization with F-actin, thereby leading to impaired actin binding and severing. Additionally, AVIL colocalized and interacted with the phospholipase enzyme PLCE1 and with the ARP2/3 actin-modulating complex. Knockdown of AVIL in human podocytes reduced actin stress fibers at the cell periphery, prevented recruitment of PLCE1 to the ARP3-rich lamellipodia, blocked EGF-induced generation of diacylglycerol (DAG) by PLCE1, and attenuated the podocyte migration rate (PMR). These effects were reversed by overexpression of WT AVIL but not by overexpression of any of the 3 patient-derived AVIL mutants. The PMR was increased by overexpression of WT Avil or PLCE1, or by EGF stimulation; however, this increased PMR was ameliorated by inhibition of the ARP2/3 complex, indicating that ARP-dependent lamellipodia formation occurs downstream of AVIL and PLCE1 function. Together, these results delineate a comprehensive pathogenic axis of SRNS that integrates loss of AVIL function with alterations in the action of PLCE1, an established SRNS protein.
Keywords: Actin-Related Protein 2-3 Complex; Cell Movement; Diglycerides; Female; Humans; Male; Microfilament Proteins; Mutation; Nephrotic Syndrome; Phosphoinositide Phospholipase C; Podocytes; Pseudopodia

Asprosin is a centrally acting orexigenic hormone. - Duerrschmid, Clemens; He, Yanlin; Wang, Chunmei; Li, Chia; Bournat, Juan C; Romere, Chase; Saha, Pradip K; Lee, Mark E; Phillips, Kevin J; Jain, Mahim; Jia, Peilin; Zhao, Zhongming; et al. (Nat Med, 2017)
Asprosin is a recently discovered fasting-induced hormone that promotes hepatic glucose production. Here we demonstrate that asprosin in the circulation crosses the blood-brain barrier and directly activates orexigenic AgRP neurons via a cAMP-dependent pathway. This signaling results in inhibition of downstream anorexigenic proopiomelanocortin (POMC)-positive neurons in a GABA-dependent manner, which then leads to appetite stimulation and a drive to accumulate adiposity and body weight. In humans, a genetic deficiency in asprosin causes a syndrome characterized by low appetite and extreme leanness; this is phenocopied by mice carrying similar mutations and can be fully rescued by asprosin. Furthermore, we found that obese humans and mice had pathologically elevated concentrations of circulating asprosin, and neutralization of asprosin in the blood with a monoclonal antibody reduced appetite and body weight in obese mice, in addition to improving their glycemic profile. Thus, in addition to performing a glucogenic function, asprosin is a centrally acting orexigenic hormone that is a potential therapeutic target in the treatment of both obesity and diabetes.
Keywords: Adolescent; Adult; Animals; Appetite Depressants; Appetite Regulation; Female; Humans; Hypothalamus; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microfilament Proteins; Neurons; Peptide Fragments; Peptide Hormones; Rats; Signal Transduction; Young Adult

Biallelic mutations in IRF8 impair human NK cell maturation and function. - Mace, Emily M; Bigley, Venetia; Gunesch, Justin T; Chinn, Ivan K; Angelo, Laura S; Care, Matthew A; Maisuria, Sheetal; Keller, Michael D; Togi, Sumihito; Watkin, Levi B; LaRosa, David F; Jhangiani, Shalini N; et al. (J Clin Invest, 2017)
Human NK cell deficiencies are rare yet result in severe and often fatal disease, particularly as a result of viral susceptibility. NK cells develop from hematopoietic stem cells, and few monogenic errors that specifically interrupt NK cell development have been reported. Here we have described biallelic mutations in IRF8, which encodes an interferon regulatory factor, as a cause of familial NK cell deficiency that results in fatal and severe viral disease. Compound heterozygous or homozygous mutations in IRF8 in 3 unrelated families resulted in a paucity of mature CD56dim NK cells and an increase in the frequency of the immature CD56bright NK cells, and this impairment in terminal maturation was also observed in Irf8-/-, but not Irf8+/-, mice. We then determined that impaired maturation was NK cell intrinsic, and gene expression analysis of human NK cell developmental subsets showed that multiple genes were dysregulated by IRF8 mutation. The phenotype was accompanied by deficient NK cell function and was stable over time. Together, these data indicate that human NK cells require IRF8 for development and functional maturation and that dysregulation of this function results in severe human disease, thereby emphasizing a critical role for NK cells in human antiviral defense.
Keywords: Alleles; Animals; CD56 Antigen; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Humans; Interferon Regulatory Factors; Killer Cells, Natural; Male; Mice; Mice, Knockout; Mutation; Virus Diseases

Biallelic mutations in the 3' exonuclease TOE1 cause pontocerebellar hypoplasia and uncover a role in snRNA processing. - Lardelli, Rea M; Schaffer, Ashleigh E; Eggens, Veerle R C; Zaki, Maha S; Grainger, Stephanie; Sathe, Shashank; Van Nostrand, Eric L; Schlachetzki, Zinayida; Rosti, Basak; Akizu, Naiara; Scott, Eric; Silhavy, Jennifer L; et al. (Nat Genet, 2017)
Deadenylases are best known for degrading the poly(A) tail during mRNA decay. The deadenylase family has expanded throughout evolution and, in mammals, consists of 12 Mg-dependent 3'-end RNases with substrate specificity that is mostly unknown. Pontocerebellar hypoplasia type 7 (PCH7) is a unique recessive syndrome characterized by neurodegeneration and ambiguous genitalia. We studied 12 human families with PCH7, uncovering biallelic, loss-of-function mutations in TOE1, which encodes an unconventional deadenylase. toe1-morphant zebrafish displayed midbrain and hindbrain degeneration, modeling PCH-like structural defects in vivo. Surprisingly, we found that TOE1 associated with small nuclear RNAs (snRNAs) incompletely processed spliceosomal. These pre-snRNAs contained 3' genome-encoded tails often followed by post-transcriptionally added adenosines. Human cells with reduced levels of TOE1 accumulated 3'-end-extended pre-snRNAs, and the immunoisolated TOE1 complex was sufficient for 3'-end maturation of snRNAs. Our findings identify the cause of a neurodegenerative syndrome linked to snRNA maturation and uncover a key factor involved in the processing of snRNA 3' ends.
Keywords: Alleles; Animals; Cerebellar Diseases; Exonucleases; Female; Humans; Male; Mice; Mutation; Neurodegenerative Diseases; Nuclear Proteins; RNA, Messenger; RNA, Small Nuclear; Spliceosomes; Zebrafish

Choices for return of primary and secondary genomic research results of 790 members of families with Mendelian disease. - Fiallos, Katie; Applegate, Carolyn; Mathews, Debra Jh; Bollinger, Juli; Bergner, Amanda L; James, Cynthia A (Eur J Hum Genet, 2017)
Although consensus is building that primary (PR) and secondary findings (SF) from genomic research should be offered to participants under some circumstances, data describing (1) actual choices of study participants and (2) factors associated with these choices are limited, hampering study planning. We conducted a cross-sectional analysis of choices made for return of PR and SF during informed consent by members of the first 247 families (790 individuals) enrolled in the Baylor-Hopkins Center for Mendelian Genomics, a genome sequencing study. Most (619; 78.3%) chose to receive SF and PR, 66 (8.4%) chose PR only, 65 (8.2%) wanted no results, and 40 (5.1%) chose SF only. Choosing SF was associated with an established clinical diagnosis in the proband (87.8 vs 79%, P=0.009) and European ancestry (EA) (87.7 vs 73%, P<0.008). Participants of non-European ancestry (NEA) were as likely as those of EA to choose SF when consented by a genetic counselor (GC) (82% NEA vs 88.3% EA, P=0.09) but significantly less likely when consented by a physician (67.4% NEA vs 85.4% EA, P=0.001). Controlling for proband diagnosis, individuals of NEA were 2.13-fold (95% CI: 1.11-4.08) more likely to choose SF when consented by a GC rather than a physician. Participants of NEA were 3-fold more likely than those of EA to decline all study results (14.7% NEA vs 5.4% EA, P<0.008). In this ethnically diverse population, whereas most participants desired PR and SF, more than 20% declined some or all results, highlighting the importance of research participant choice.
Keywords: Databases, Genetic; Female; Genetic Diseases, Inborn; Genome, Human; Genome-Wide Association Study; Humans; Male; Pedigree; Research Subjects

Clinical report: A patient with a late diagnosis of cerebrotendinous xanthomatosis and a response to treatment. - Alhariri, Ahmad; Hamilton, Katherine; Oza, Vikash; Cordoro, Kelly; Sobreira, Nara L; Malloy, Mary; Slavotinek, Anne (Am J Med Genet A, 2017)
Cerebrotendinous xanthomatosis (CTX) is a rare, autosomal recessive, inborn error of bile acid metabolism characterized by diarrhea in infancy, juvenile cataracts in childhood, tendon xanthomas developing in the second to third decades of life, and progressive neurologic dysfunction in adulthood. The condition is caused by mutations in the CYP27A1 gene that result in decreased production of chenodeoxycholic acid (CDCA) and elevated levels of cholestanol and bile alcohols. We present a 36-year-old male of Han ethnicity who developed xanthomas of his Achilles tendons and suffered neurocognitive declines and gait deterioration in his second decade. The diagnosis of CTX was confirmed by marked elevation of the serum cholestanol level. Sequencing of CYP27A1 showed a paternally inherited splice mutation, c.446 + 1G>T, and a maternally inherited nonsense mutation, c.808C>T, predicting p.(Arg270*). Despite the advanced disease in this patient, treatment with CDCA reduced the xanthoma size and improved his cognition and strength, and the patient made significant gains in his ambulation and coordination. We report this case to illustrate the potential benefits of therapy in patients with CTX who have advanced disease at the time of diagnosis.
Keywords: Achilles Tendon; Adult; Bile Acids and Salts; Chenodeoxycholic Acid; Cholestanetriol 26-Monooxygenase; Cholestanol; Codon, Nonsense; Humans; Male; Xanthomatosis, Cerebrotendinous

Clinically severe CACNA1A alleles affect synaptic function and neurodegeneration differentially. - Luo, Xi; Rosenfeld, Jill A; Yamamoto, Shinya; Harel, Tamar; Zuo, Zhongyuan; Hall, Melissa; Wierenga, Klaas J; Pastore, Matthew T; Bartholomew, Dennis; Delgado, Mauricio R; Rotenberg, Joshua; Lewis, Richard Alan; et al. (PLoS Genet, 2017)
Dominant mutations in CACNA1A, encoding the α-1A subunit of the neuronal P/Q type voltage-dependent Ca2+ channel, can cause diverse neurological phenotypes. Rare cases of markedly severe early onset developmental delay and congenital ataxia can be due to de novo CACNA1A missense alleles, with variants affecting the S4 transmembrane segments of the channel, some of which are reported to be loss-of-function. Exome sequencing in five individuals with severe early onset ataxia identified one novel variant (p.R1673P), in a girl with global developmental delay and progressive cerebellar atrophy, and a recurrent, de novo p.R1664Q variant, in four individuals with global developmental delay, hypotonia, and ophthalmologic abnormalities. Given the severity of these phenotypes we explored their functional impact in Drosophila. We previously generated null and partial loss-of-function alleles of cac, the homolog of CACNA1A in Drosophila. Here, we created transgenic wild type and mutant genomic rescue constructs with the two noted conserved point mutations. The p.R1673P mutant failed to rescue cac lethality, displayed a gain-of-function phenotype in electroretinograms (ERG) recorded from mutant clones, and evolved a neurodegenerative phenotype in aging flies, based on ERGs and transmission electron microscopy. In contrast, the p.R1664Q variant exhibited loss of function and failed to develop a neurodegenerative phenotype. Hence, the novel R1673P allele produces neurodegenerative phenotypes in flies and human, likely due to a toxic gain of function.
Keywords: Alleles; Animals; Animals, Genetically Modified; Calcium Channels; Cerebellar Ataxia; Child; Child, Preschool; Drosophila melanogaster; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Microscopy, Electron, Transmission; Mutation, Missense; Neurodegenerative Diseases; Neuroimaging; Phenotype; Point Mutation

Complex phenotypes associated with STIM1 mutations in both coiled coil and EF-hand domains. - Harris, Elizabeth; Burki, Umar; Marini-Bettolo, Chiara; Neri, Marcella; Scotton, Chiara; Hudson, Judith; Bertoli, Marta; Evangelista, Teresinha; Vroling, Bas; Polvikoski, Tuomo; Roberts, Mark; Topf, Ana; et al. (Neuromuscul Disord, 2017)
Dominant mutations in STIM1 are a cause of three allelic conditions: tubular aggregate myopathy, Stormorken syndrome (a complex phenotype including myopathy, hyposplenism, hypocalcaemia and bleeding diathesis), and a platelet dysfunction disorder, York platelet syndrome. Previous reports have suggested a genotype-phenotype correlation with mutations in the N-terminal EF-hand domain associated with tubular aggregate myopathy, and a common mutation at p.R304W in a coiled coil domain associated with Stormorken syndrome. In this study individuals with STIM1 variants were identified by exome sequencing or STIM1 direct sequencing, and assessed for neuromuscular, haematological and biochemical evidence of the allelic disorders of STIM1. STIM1 mutations were investigated by fibroblast calcium imaging and 3D modelling. Six individuals with STIM1 mutations, including two novel mutations (c.262A>G (p.S88G) and c.911G>A (p.R304Q)), were identified. Extra-neuromuscular symptoms including thrombocytopenia, platelet dysfunction, hypocalcaemia or hyposplenism were present in 5/6 patients with mutations in both the EF-hand and CC domains. 3/6 patients had psychiatric disorders, not previously reported in STIM1 disease. Review of published STIM1 patients (n = 49) confirmed that neuromuscular symptoms are present in most patients. We conclude that the phenotype associated with activating STIM1 mutations frequently includes extra-neuromuscular features such as hypocalcaemia, hypo-/asplenia and platelet dysfunction regardless of mutation domain.
Keywords: Adult; Blood Platelet Disorders; Calcium; Cell Culture Techniques; DNA Mutational Analysis; Dyslexia; Erythrocytes, Abnormal; Family Health; Female; Fibroblasts; Genetic Association Studies; Humans; Ichthyosis; Magnetic Resonance Imaging; Male; Microscopy, Electron; Middle Aged; Migraine Disorders; Miosis; Models, Molecular; Muscle Fatigue; Muscle, Skeletal; Mutation; Myopathies, Structural, Congenital; NAD; Neoplasm Proteins; Spleen; Stromal Interaction Molecule 1

Congenital heart defects and left ventricular non-compaction in males with loss-of-function variants in NONO. - Scott, Daryl A; Hernandez-Garcia, Andres; Azamian, Mahshid S; Jordan, Valerie K; Kim, Bum Jun; Starkovich, Molly; Zhang, Jinglan; Wong, Lee-Jun; Darilek, Sandra A; Breman, Amy M; Yang, Yaping; Lupski, James R; et al. (J Med Genet, 2017)
BACKGROUND: The non-POU domain containing octamer-binding gene (NONO) is located on chromosome Xq13.1 and encodes a member of a small family of RNA-binding and DNA-binding proteins that perform a variety of tasks involved in RNA synthesis, transcriptional regulation and DNA repair. Loss-of-function variants in NONO have been described as a cause of intellectual disability in males but have not been described in association with congenital heart defects or cardiomyopathy. In this article, we seek to further define the phenotypic consequences of NONO depletion in human subjects. METHODS: We searched a clinical database of over 6000 individuals referred for exome sequencing and over 60 000 individuals referred for CNV analysis. RESULTS: We identified two males with atrial and ventricular septal defects, left ventricular non-compaction (LVNC), developmental delay and intellectual disability, who harboured de novo, loss-of-function variants in NONO. We also identified a male infant with developmental delay, congenital brain anomalies and severe LVNC requiring cardiac transplantation, who inherited a single-gene deletion of NONO from his asymptomatic mother. CONCLUSIONS: We conclude that in addition to global developmental delay and intellectual disability, males with loss-of-function variants in NONO may also be predisposed to developing congenital heart defects and LVNC with the penetrance of these cardiac-related problems being influenced by genetic, epigenetic, environmental or stochastic factors. Brain imaging of males with NONO deficiency may reveal structural defects with abnormalities of the corpus callosum being the most common. Although dysmorphic features vary between affected individuals, relative macrocephaly is a common feature.
Keywords: Child; Child, Preschool; Developmental Disabilities; DNA-Binding Proteins; Exome; Heart Defects, Congenital; Heart Ventricles; Humans; Infant; Male; Nuclear Matrix-Associated Proteins; Octamer Transcription Factors; RNA-Binding Proteins

Contribution of rare inherited and de novo variants in 2,871 congenital heart disease probands. - Jin, Sheng Chih; Homsy, Jason; Zaidi, Samir; Lu, Qiongshi; Morton, Sarah; DePalma, Steven R; Zeng, Xue; Qi, Hongjian; Chang, Weni; Sierant, Michael C; Hung, Wei-Chien; Haider, Shozeb; et al. (Nat Genet, 2017)
Congenital heart disease (CHD) is the leading cause of mortality from birth defects. Here, exome sequencing of a single cohort of 2,871 CHD probands, including 2,645 parent-offspring trios, implicated rare inherited mutations in 1.8%, including a recessive founder mutation in GDF1 accounting for ∼5% of severe CHD in Ashkenazim, recessive genotypes in MYH6 accounting for ∼11% of Shone complex, and dominant FLT4 mutations accounting for 2.3% of Tetralogy of Fallot. De novo mutations (DNMs) accounted for 8% of cases, including ∼3% of isolated CHD patients and ∼28% with both neurodevelopmental and extra-cardiac congenital anomalies. Seven genes surpassed thresholds for genome-wide significance, and 12 genes not previously implicated in CHD had >70% probability of being disease related. DNMs in ∼440 genes were inferred to contribute to CHD. Striking overlap between genes with damaging DNMs in probands with CHD and autism was also found.
Keywords: Adult; Autistic Disorder; Cardiac Myosins; Case-Control Studies; Child; Exome; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Growth Differentiation Factor 1; Heart Defects, Congenital; Heterozygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Mutation; Myosin Heavy Chains; Pedigree; Risk; Vascular Endothelial Growth Factor Receptor-3

Copy Number Changes Identified Using Whole Exome Sequencing in Nonsyndromic Cleft Lip and Palate in a Honduran Population. - Cai, Yi; Patterson, Karynne E; Reinier, Frederic; Keesecker, Sarah E; Blue, Elizabeth; Bamshad, Michael; Haddad, Joseph (Birth Defects Res, 2017)
BACKGROUND: The majority of cleft lip with or without cleft palate cases appear as an isolated, nonsyndromic entity (NSCLP). With the advent of next generation sequencing, whole exome sequencing (WES) has been used to identify single nucleotide variants and insertion/deletions which cause or increase the risk of NSCLP. However, to our knowledge, there are no published studies using WES in NSCLP to investigate copy number changes (CNCs), which are a major component of human genetic variation. Our study aimed to identify CNCs associated with NSCLP in a Honduran population using WES. METHODS: WES was performed on two to four members of 27 multiplex Honduran families. CNCs were identified using two algorithms, CoNIFER and XHMM. Priority was given to CNCs that were identified in more than one patient and had variant frequencies of less than 5% in reference data sets. RESULTS: WES completion was defined as >90% of the WES target at >8 × coverage and >80% of the WES target at >20 × coverage. Twenty-four CNCs that met our inclusion criteria were identified by both CoNIFER and XHMM. These CNCs were confirmed using quantitative PCR. Pedigree analysis produced three CNCs corresponding to ADH7, AHR, and CRYZ segregating with NSCLP. Two of the three CNCs implicate genes, AHR and ADH7, whose known biological functions could plausibly play a role in NSCLP. CONCLUSION: WES can be used to detect candidate CNCs that may be involved in the pathophysiology of NSCLP. Birth Defects Research 109:1257-1267, 2017. © 2017 Wiley Periodicals, Inc.
Keywords: Adolescent; Adult; Alcohol Dehydrogenase; Alleles; Basic Helix-Loop-Helix Transcription Factors; Child; Child, Preschool; Cleft Lip; Cleft Palate; DNA Copy Number Variations; Family; Female; Gene Frequency; Genetic Variation; High-Throughput Nucleotide Sequencing; Honduras; Humans; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Receptors, Aryl Hydrocarbon; Whole Exome Sequencing

Corner fracture type spondylometaphyseal dysplasia: Overlap with type II collagenopathies. - Machol, Keren; Jain, Mahim; Almannai, Mohammed; Orand, Thibault; Lu, James T; Tran, Alyssa; Chen, Yuqing; Schlesinger, Alan; Gibbs, Richard; Bonafe, Luisa; Campos-Xavier, Ana Belinda; Unger, Sheila; et al. (Am J Med Genet A, 2017)
Spondylometaphyseal dysplasia (SMD) corner fracture type (also known as SMD "Sutcliffe" type, MIM 184255) is a rare skeletal dysplasia that presents with mild to moderate short stature, developmental coxa vara, mild platyspondyly, corner fracture-like lesions, and metaphyseal abnormalities with sparing of the epiphyses. The molecular basis for this disorder has yet to be clarified. We describe two patients with SMD corner fracture type and heterozygous pathogenic variants in COL2A1. These two cases together with a third case of SMD corner fracture type with a heterozygous COL2A1 pathogenic variant previously described suggest that this disorder overlaps with type II collagenopathies. The finding of one of the pathogenic variants in a previously reported case of spondyloepimetaphyseal dysplasia (SEMD) Strudwick type and the significant clinical similarity suggest an overlap between SMD corner fracture and SEMD Strudwick types. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Amino Acid Substitution; Bone Diseases, Developmental; Child, Preschool; Collagen Type II; Diagnosis, Differential; Exome; Genetic Association Studies; Genotype; Growth Disorders; High-Throughput Nucleotide Sequencing; Hip Joint; Humans; Infant; Male; Mutation; Osteochondrodysplasias; Phenotype; Radiography; Tibial Fractures

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder. - Küry, Sébastien; Besnard, Thomas; Ebstein, Frédéric; Khan, Tahir N; Gambin, Tomasz; Douglas, Jessica; Bacino, Carlos A; Craigen, William J; Sanders, Stephan J; Lehmann, Andrea; Latypova, Xénia; Khan, Kamal; et al. (Am J Hum Genet, 2017)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with intellectual disability, congenital malformations, ophthalmologic anomalies, feeding difficulties, deafness, and subtle dysmorphic facial features. We observed reduced PSMD12 levels and an accumulation of ubiquitinated proteins without any impairment of proteasome catalytic activity. Our PSMD12 loss-of-function zebrafish CRISPR/Cas9 model exhibited microcephaly, decreased convolution of the renal tubules, and abnormal craniofacial morphology. Our data support the biological importance of PSMD12 as a scaffolding subunit in proteasome function during development and neurogenesis in particular; they enable the definition of a neurodevelopmental disorder due to PSMD12 variants, expanding the phenotypic spectrum of UPS-dependent disorders.
Keywords: Adolescent; Animals; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Down-Regulation; Female; Gene Deletion; Humans; Infant; Intellectual Disability; Male; Microcephaly; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Proteasome Endopeptidase Complex; Zebrafish

De Novo Missense Mutations in DHX30 Impair Global Translation and Cause a Neurodevelopmental Disorder. - Lessel, Davor; Schob, Claudia; Küry, Sébastien; Reijnders, Margot R F; Harel, Tamar; Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Denecke, Jonas; Edvardson, Shimon; Colin, Estelle; Stegmann, Alexander P A; Gerkes, Erica H; et al. (Am J Hum Genet, 2017)
DHX30 is a member of the family of DExH-box helicases, which use ATP hydrolysis to unwind RNA secondary structures. Here we identified six different de novo missense mutations in DHX30 in twelve unrelated individuals affected by global developmental delay (GDD), intellectual disability (ID), severe speech impairment and gait abnormalities. While four mutations are recurrent, two are unique with one affecting the codon of one recurrent mutation. All amino acid changes are located within highly conserved helicase motifs and were found to either impair ATPase activity or RNA recognition in different in vitro assays. Moreover, protein variants exhibit an increased propensity to trigger stress granule (SG) formation resulting in global translation inhibition. Thus, our findings highlight the prominent role of translation control in development and function of the central nervous system and also provide molecular insight into how DHX30 dysfunction might cause a neurodevelopmental disorder.
Keywords: Adenosine Triphosphatases; Adolescent; Amino Acids; Cell Line; Cell Line, Tumor; Central Nervous System; Child; Child, Preschool; Developmental Disabilities; Female; HEK293 Cells; Humans; Intellectual Disability; Male; Mutation, Missense; RNA; RNA Helicases

De novo mutations in HNRNPU result in a neurodevelopmental syndrome. - Yates, T Michael; Vasudevan, Pradeep C; Chandler, Kate E; Donnelly, Deirdre E; Stark, Zornitza; Sadedin, Simon; Willoughby, Josh; Balasubramanian, Meena (Am J Med Genet A, 2017)
Exome sequencing in the context of developmental disorders is a useful technique, but variants found need to be interpreted in the context of detailed phenotypic information. Whole gene deletions and loss-of-function-mutations in the HNRNPU gene have been associated with intellectual disability and seizures in some patients. However, a unifying syndromic phenotype has not been previously elucidated. Here, we report a total of seven patients (six patients identified through the Wellcome Trust Deciphering Developmental Disorders study, with one additional patient), who have heterozygous de novo mutations in HNRNPU. These were found via trio-based exome sequencing. All but one of the mutations is predicted to cause loss-of-function. These patients have dysmorphic features in common, including prominent eyebrows, long palpebral fissures, overhanging columella, and thin upper lip. All patients have developmental delay and intellectual disability (ID), ranging from moderate to severe. Seizures are common from early childhood. These initially occur in the context of febrile episodes. This series demonstrates common phenotypic features, including emerging dysmorphism, associated with heterozygous HNRNPU mutations. This allows us to define a novel neurodevelopmental syndrome, with a likely mechanism of haploinsufficiency.
Keywords: Adolescent; Adult; Child; Child, Preschool; Developmental Disabilities; Exome; Female; Genetic Predisposition to Disease; Haploinsufficiency; Heterogeneous-Nuclear Ribonucleoprotein U; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Neurodevelopmental Disorders; Phenotype; Seizures; Young Adult

De novo mutations in inhibitors of Wnt, BMP, and Ras/ERK signaling pathways in non-syndromic midline craniosynostosis. - Timberlake, Andrew T; Furey, Charuta G; Choi, Jungmin; Nelson-Williams, Carol; Loring, Erin; Galm, Amy; Kahle, Kristopher T; Steinbacher, Derek M; Larysz, Dawid; Persing, John A; Lifton, Richard P (Proc Natl Acad Sci U S A, 2017)
Non-syndromic craniosynostosis (NSC) is a frequent congenital malformation in which one or more cranial sutures fuse prematurely. Mutations causing rare syndromic craniosynostoses in humans and engineered mouse models commonly increase signaling of the Wnt, bone morphogenetic protein (BMP), or Ras/ERK pathways, converging on shared nuclear targets that promote bone formation. In contrast, the genetics of NSC is largely unexplored. More than 95% of NSC is sporadic, suggesting a role for de novo mutations. Exome sequencing of 291 parent-offspring trios with midline NSC revealed 15 probands with heterozygous damaging de novo mutations in 12 negative regulators of Wnt, BMP, and Ras/ERK signaling (10.9-fold enrichment, = 2.4 × 10). had 4 de novo and 14 transmitted mutations; no other gene had more than 1. Four familial NSC kindreds had mutations in genes previously implicated in syndromic disease. Collectively, these mutations contribute to 10% of probands. Mutations are predominantly loss-of-function, implicating haploinsufficiency as a frequent mechanism. A common risk variant near increased the penetrance of mutations and was overtransmitted to patients with de novo mutations in other genes in these pathways, supporting a frequent two-locus pathogenesis. These findings implicate new genes in NSC and demonstrate related pathophysiology of common non-syndromic and rare syndromic craniosynostoses. These findings have implications for diagnosis, risk of recurrence, and risk of adverse neurodevelopmental outcomes. Finally, the use of pathways identified in rare syndromic disease to find genes accounting for non-syndromic cases may prove broadly relevant to understanding other congenital disorders featuring high locus heterogeneity.
Keywords: Adult; Animals; Bone Morphogenetic Proteins; Child; Child, Preschool; Cranial Sutures; Craniosynostoses; Exome; Female; Humans; Male; MAP Kinase Signaling System; Mutation; Osteogenesis; Penetrance; Phenotype; ras Proteins; Sequence Analysis, DNA; Signal Transduction; Smad6 Protein; Whole Exome Sequencing

A defect in myoblast fusion underlies Carey-Fineman-Ziter syndrome. - Di Gioia, Silvio Alessandro; Connors, Samantha; Matsunami, Norisada; Cannavino, Jessica; Rose, Matthew F; Gilette, Nicole M; Artoni, Pietro; de Macena Sobreira, Nara Lygia; Chan, Wai-Man; Webb, Bryn D; Robson, Caroline D; Cheng, Long; et al. (Nat Commun, 2017)
Multinucleate cellular syncytial formation is a hallmark of skeletal muscle differentiation. Myomaker, encoded by Mymk (Tmem8c), is a well-conserved plasma membrane protein required for myoblast fusion to form multinucleated myotubes in mouse, chick, and zebrafish. Here, we report that autosomal recessive mutations in MYMK (OMIM 615345) cause Carey-Fineman-Ziter syndrome in humans (CFZS; OMIM 254940) by reducing but not eliminating MYMK function. We characterize MYMK-CFZS as a congenital myopathy with marked facial weakness and additional clinical and pathologic features that distinguish it from other congenital neuromuscular syndromes. We show that a heterologous cell fusion assay in vitro and allelic complementation experiments in mymk knockdown and mymk zebrafish in vivo can differentiate between MYMK wild type, hypomorphic and null alleles. Collectively, these data establish that MYMK activity is necessary for normal muscle development and maintenance in humans, and expand the spectrum of congenital myopathies to include cell-cell fusion deficits.
Keywords: Adult; Amino Acid Sequence; Animals; Cell Fusion; Child; Disease Models, Animal; Embryo, Nonmammalian; Female; Gene Expression; Genes, Recessive; Genetic Complementation Test; Humans; Infant; Male; Membrane Proteins; Mobius Syndrome; Morphogenesis; Muscle Proteins; Muscle, Skeletal; Muscular Diseases; Mutation; Myoblasts; Pedigree; Pierre Robin Syndrome; Sequence Alignment; Sequence Homology, Amino Acid; Zebrafish; Zebrafish Proteins

denovo-db: a compendium of human de novo variants. - Turner, Tychele N; Yi, Qian; Krumm, Niklas; Huddleston, John; Hoekzema, Kendra; F Stessman, Holly A; Doebley, Anna-Lisa; Bernier, Raphael A; Nickerson, Deborah A; Eichler, Evan E (Nucleic Acids Res, 2017)
Whole-exome and whole-genome sequencing have facilitated the large-scale discovery of de novo variants in human disease. To date, most de novo discovery through next-generation sequencing focused on congenital heart disease and neurodevelopmental disorders (NDDs). Currently, de novo variants are one of the most significant risk factors for NDDs with a substantial overlap of genes involved in more than one NDD. To facilitate better usage of published data, provide standardization of annotation, and improve accessibility, we created denovo-db (http://denovo-db.gs.washington.edu), a database for human de novo variants. As of July 2016, denovo-db contained 40 different studies and 32,991 de novo variants from 23,098 trios. Database features include basic variant information (chromosome location, change, type); detailed annotation at the transcript and protein levels; severity scores; frequency; validation status; and, most importantly, the phenotype of the individual with the variant. We included a feature on our browsable website to download any query result, including a downloadable file of the full database with additional variant details. denovo-db provides necessary information for researchers to compare their data to other individuals with the same phenotype and also to controls allowing for a better understanding of the biology of de novo variants and their contribution to disease.
Keywords: Computational Biology; Databases, Nucleic Acid; Genetic Association Studies; Genetic Variation; Germ-Line Mutation; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Web Browser

Diagnosis of Chronic Intestinal Pseudo-obstruction and Megacystis by Sequencing the ACTG2 Gene. - Milunsky, Aubrey; Baldwin, Clinton; Zhang, Xiaoying; Primack, Daniel; Curnow, Adrian; Milunsky, Jeff (J Pediatr Gastroenterol Nutr, 2017)
OBJECTIVES: The diagnosis of chronic intestinal pseudo-obstruction has depended on clinical features, manometry, and imaging. This report aimed to determine the efficacy of sequencing the actin γ-2 (ACTG2) gene for diagnosis. In addition, the goal was to determine how often a mutation would be found in our randomly collected cohort of probands and those probands published previously. METHODS: Whole exome sequencing was performed in 4 probands with chronic intestinal pseudo-obstruction. Subsequently, only the ACTG2 gene was sequenced in another 24 probands (total 28). We analyzed published data of 83 probands and our 28 (total 111) and determined how many had pathogenic variants and the precise genotype. RESULTS: Whole exome and Sanger sequencing revealed a pathogenic variant in the ACTG2 gene in 4 out of 28 of our probands and in 45 out of 83 published probands (49/111 [44.1%]). Moreover, a mutational hotspot in the ACTG2 gene was recognized. Genetic heterogeneity is evident. CONCLUSIONS: Pooled gene sequencing results from 1 individual in each of 111 families enabled a precise diagnosis of an ACTG2 mutation in 49 (44%). The benefit to patients and families of early confirmation of a motility disorder not only helps avoid unnecessary intervention, but also enables institution of appropriate treatments and avoidance of secondary disorders such as malnutrition and poor growth. Knowledge of a pathogenic variant in a parent, with a 50% risk of recurrence, provides an opportunity for genetic counseling.
Keywords: Actins; Adult; Child; Child, Preschool; Chronic Disease; Duodenum; Female; Fetal Diseases; Genetic Markers; Genetic Testing; Humans; Infant; Infant, Newborn; Intestinal Pseudo-Obstruction; Male; Mutation; Sequence Analysis, DNA; Urinary Bladder; Whole Exome Sequencing

Disruptions in asymmetric centrosome inheritance and WDR62-Aurora kinase B interactions in primary microcephaly. - Sgourdou, Paraskevi; Mishra-Gorur, Ketu; Saotome, Ichiko; Henagariu, Octavian; Tuysuz, Beyhan; Campos, Cynthia; Ishigame, Keiko; Giannikou, Krinio; Quon, Jennifer L; Šestan, Nenad; Çağlayan, Ahmet O; Günel, Murat; et al. (Sci Rep, 2017)
Recessive mutations in WD repeat domain 62 (WDR62) cause microcephaly and a wide spectrum of severe brain malformations. Disruption of the mouse ortholog results in microcephaly underlain by reduced proliferation of neocortical progenitors during late neurogenesis, abnormalities in asymmetric centrosome inheritance leading to neuronal migration delays, and altered neuronal differentiation. Spindle pole localization of WDR62 and mitotic progression are defective in patient-derived fibroblasts, which, similar to mouse neocortical progenitors, transiently arrest at prometaphase. Expression of WDR62 is closely correlated with components of the chromosome passenger complex (CPC), a key regulator of mitosis. Wild type WDR62, but not disease-associated mutant forms, interacts with the CPC core enzyme Aurora kinase B and staining of CPC components at centromeres is altered in patient-derived fibroblasts. Our findings demonstrate critical and diverse functions of WDR62 in neocortical development and provide insight into the mechanisms by which its disruption leads to a plethora of structural abnormalities.
Keywords: Animals; Aurora Kinase B; Brain; Cell Cycle; Cell Differentiation; Cell Proliferation; Centrosome; Consanguinity; Disease Models, Animal; Epistasis, Genetic; Fluorescent Antibody Technique; Gene Expression; Humans; Inheritance Patterns; Male; Mice; Mice, Knockout; Microcephaly; Mutation; Nerve Tissue Proteins; Neural Stem Cells; Pedigree; Whole Genome Sequencing

A Dominant Mutation in Nuclear Receptor Interacting Protein 1 Causes Urinary Tract Malformations Dysregulation of Retinoic Acid Signaling. - Vivante, Asaf; Mann, Nina; Yonath, Hagith; Weiss, Anna-Carina; Getwan, Maike; Kaminski, Michael M; Bohnenpoll, Tobias; Teyssier, Catherine; Chen, Jing; Shril, Shirlee; van der Ven, Amelie T; Ityel, Hadas; et al. (J Am Soc Nephrol, 2017)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of CKD in the first three decades of life. However, for most patients with CAKUT, the causative mutation remains unknown. We identified a kindred with an autosomal dominant form of CAKUT. By whole-exome sequencing, we identified a heterozygous truncating mutation (c.279delG, p.Trp93fs*) of the nuclear receptor interacting protein 1 gene () in all seven affected members. encodes a nuclear receptor transcriptional cofactor that directly interacts with the retinoic acid receptors (RARs) to modulate retinoic acid transcriptional activity. Unlike wild-type NRIP1, the altered NRIP1 protein did not translocate to the nucleus, did not interact with RAR, and failed to inhibit retinoic acid-dependent transcriptional activity upon expression in HEK293 cells. Notably, we also showed that treatment with retinoic acid enhanced NRIP1 binding to RAR RNA hybridization confirmed expression in the developing urogenital system of the mouse. In explant cultures of embryonic kidney rudiments, retinoic acid stimulated expression, whereas a pan-RAR antagonist strongly reduced it. Furthermore, mice heterozygous for a null allele of showed a CAKUT-spectrum phenotype. Finally, expression and knockdown experiments in confirmed an evolutionarily conserved role for in renal development. These data indicate that dominant mutations can cause CAKUT by interference with retinoic acid transcriptional signaling, shedding light on the well documented association between abnormal vitamin A levels and renal malformations in humans, and suggest a possible gene-environment pathomechanism in this disease.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Mice; Mutation; Nuclear Proteins; Nuclear Receptor Interacting Protein 1; Signal Transduction; Tretinoin; Urinary Tract

Dominant Transmission Observed in Adolescents and Families With Orthostatic Intolerance. - Posey, Jennifer E; Martinez, Rebecca; Lankford, Jeremy E; Lupski, James R; Numan, Mohammed T; Butler, Ian J (Pediatr Neurol, 2017)
BACKGROUND: Orthostatic intolerance is typically thought to be sporadic and attributed to cerebral autonomic dysfunction. We sought to identify families with inherited autonomic dysfunction manifest as symptomatic orthostatic intolerance to characterize mode of inheritance and clinical features. METHODS: Sixteen families with two or more first- or second-degree relatives with autonomic dysfunction and orthostatic intolerance were enrolled. A clinical diagnosis of autonomic dysfunction defined by symptomatic orthostatic intolerance diagnosed by head-up tilt table testing was confirmed for each proband. Clinical features and evaluation were obtained from each proband using a standardized intake questionnaire, and family history information was obtained from probands and available relatives. RESULTS: Comprehensive pedigree analysis of 16 families (39 individuals with orthostatic intolerance and 40 individuals suspected of having orthostatic intolerance) demonstrated dominant transmission of autonomic dysfunction with incomplete penetrance. Affected individuals were predominantly female (71.8%, 28/39; F:M, 2.5:1). Male-to-male transmission, although less common, was observed and demonstrated to transmit through unaffected males with an affected parent. Similar to sporadic orthostatic intolerance, probands report a range of symptoms across multiple organ systems, with headaches and neuromuscular features being most common. CONCLUSIONS: Familial occurrence and vertical transmission of autonomic dysfunction in 16 families suggest a novel genetic syndrome with dominant transmission, incomplete penetrance, and skewing of the sex ratio. Elucidation of potential genetic contributions to orthostatic intolerance may inform therapeutic management and identification of individuals at risk. Adolescent evaluation should include identification and treatment of potential at-risk relatives.
Keywords: Adolescent; Cohort Studies; Family; Female; Genetic Testing; Humans; Male; Orthostatic Intolerance; Pedigree; Posture; Surveys and Questionnaires; Tilt-Table Test

Dual molecular diagnosis contributes to atypical Prader-Willi phenotype in monozygotic twins. - Jehee, Fernanda S; de Oliveira, Valdirene T; Gurgel-Giannetti, Juliana; Pietra, Rafaella X; Rubatino, Fernando V M; Carobin, Natália V; Vianna, Gabrielle S; de Freitas, Mariana L; Fernandes, Karla S; Ribeiro, Beatriz S V; Brüggenwirth, Hennie T; Ali-Amin, Roza; et al. (Am J Med Genet A, 2017)
We describe monozygotic twin girls with genetic variation at two separate loci resulting in a blended phenotype of Prader-Willi syndrome and Pitt-Hopkins syndrome. These girls were diagnosed in early infancy with Prader-Willi syndrome, but developed an atypical phenotype, with apparent intellectual deficiency and lack of obesity. Array-comparative genomic hybridization confirmed a de novo paternal deletion of the 15q11.2q13 region and exome sequencing identified a second mutational event in both girls, which was a novel variant c.145+1G>A affecting a TCF4 canonical splicing site inherited from the mosaic mother. RNA studies showed that the variant abolished the donor splicing site, which was accompanied by activation of an alternative non-canonical splicing-site which then predicts a premature stop codon in the following exon. Clinical re-evaluation of the twins indicated that both variants are likely contributing to the more severe phenotypic presentation. Our data show that atypical clinical presentations may actually be the expression of blended clinical phenotypes arising from independent pathogenic events at two loci.
Keywords: Adolescent; Base Sequence; Child; Chromosome Deletion; Chromosomes, Human, Pair 15; Comparative Genomic Hybridization; Exome; Facies; Female; Humans; Hyperventilation; Intellectual Disability; Obesity; Pathology, Molecular; Phenotype; Prader-Willi Syndrome; Transcription Factor 4; Twins, Monozygotic

DUOX2 Gene Mutation Manifesting as Resistance to Thyrotropin Phenotype. - Srichomkwun, Panudda; Takamatsu, Junta; Nickerson, Deborah A; Bamshad, Michael J; Chong, Jessica X; Refetoff, Samuel (Thyroid, 2017)
Resistance to thyrotropin (TSH) (RTSH; defined by elevated TSH and a normal or hypoplastic thyroid gland) can be caused by mutations in genes encoding the TSH receptor and PAX8, and it has been linked to a locus on chromosome 15. In two nonconsanguineous families with nongoitrous euthyroid hyperthyrotropinemia, typical of the RTSH phenotype, exome analysis identified five rare DUOX2 gene variants (p.A649E, p.P1391A, p.R885L, p.G488R, and p.SF965-6SfsX29) found to be pathogenic. This form of nongoitrous dyshormonogenesis masquerades both clinically and biochemically as RTSH. Accordingly, mutations in DUOX2 should be added to those of SLC26A4 as causes of RTSH.
Keywords: Child, Preschool; Congenital Hypothyroidism; Dual Oxidases; Female; Genotype; Humans; Male; Mutation; Pedigree; Phenotype; Thyroid Hormone Resistance Syndrome; Thyrotropin

Efficient CNV breakpoint analysis reveals unexpected structural complexity and correlation of dosage-sensitive genes with clinical severity in genomic disorders. - Zhang, Ling; Wang, Jingmin; Zhang, Cheng; Li, Dongxiao; Carvalho, Claudia M B; Ji, Haoran; Xiao, Jianqiu; Wu, Ye; Zhou, Weichen; Wang, Hongyan; Jin, Li; Luo, Yang; et al. (Hum Mol Genet, 2017)
Genomic disorders are the clinical conditions manifested by submicroscopic genomic rearrangements including copy number variants (CNVs). The CNVs can be identified by array-based comparative genomic hybridization (aCGH), the most commonly used technology for molecular diagnostics of genomic disorders. However, clinical aCGH only informs CNVs in the probe-interrogated regions. Neither orientational information nor the resulting genomic rearrangement structure is provided, which is a key to uncovering mutational and pathogenic mechanisms underlying genomic disorders. Long-range polymerase chain reaction (PCR) is a traditional approach to obtain CNV breakpoint junction, but this method is inefficient when challenged by structural complexity such as often found at the PLP1 locus in association with Pelizaeus-Merzbacher disease (PMD). Here we introduced 'capture and single-molecule real-time sequencing' (cap-SMRT-seq) and newly developed 'asymmetry linker-mediated nested PCR walking' (ALN-walking) for CNV breakpoint sequencing in 49 subjects with PMD-associated CNVs. Remarkably, 29 (94%) of the 31 CNV breakpoint junctions unobtainable by conventional long-range PCR were resolved by cap-SMRT-seq and ALN-walking. Notably, unexpected CNV complexities, including inter-chromosomal rearrangements that cannot be resolved by aCGH, were revealed by efficient breakpoint sequencing. These sequence-based structures of PMD-associated CNVs further support the role of DNA replicative mechanisms in CNV mutagenesis, and facilitate genotype-phenotype correlation studies. Intriguingly, the lengths of gained segments by CNVs are strongly correlated with clinical severity in PMD, potentially reflecting the functional contribution of other dosage-sensitive genes besides PLP1. Our study provides new efficient experimental approaches (especially ALN-walking) for CNV breakpoint sequencing and highlights their importance in uncovering CNV mutagenesis and pathogenesis in genomic disorders.
Keywords: Base Sequence; Comparative Genomic Hybridization; DNA Copy Number Variations; DNA Replication; Female; Gene Dosage; Gene Duplication; Gene Rearrangement; Genetic Association Studies; Genome, Human; Genomics; Humans; Male; Mutation; Pelizaeus-Merzbacher Disease; Sequence Analysis, DNA

Encephalopathy caused by novel mutations in the CMP-sialic acid transporter, SLC35A1. - Ng, Bobby G; Asteggiano, Carla G; Kircher, Martin; Buckingham, Kati J; Raymond, Kimiyo; Nickerson, Deborah A; Shendure, Jay; Bamshad, Michael J; Ensslen, Matthias; Freeze, Hudson H (Am J Med Genet A, 2017)
Transport of activated nucleotide-sugars into the Golgi is critical for proper glycosylation and mutations in these transporters cause a group of rare genetic disorders termed congenital disorders of glycosylation. We performed exome sequencing on an individual with a profound neurological presentation and identified rare compound heterozygous mutations, p.Thr156Arg and p.Glu196Lys, in the CMP-sialic acid transporter, SLC35A1. Patient primary fibroblasts and serum showed a considerable decrease in the amount of N- and O-glycans terminating in sialic acid. Direct measurement of CMP-sialic acid transport into the Golgi showed a substantial decrease in overall rate of transport. Here we report the identification of the third patient with CMP-sialic acid transporter deficiency, who presented with severe neurological phenotype, but without hematological abnormalities.
Keywords: Animals; Brain Diseases; Child; CHO Cells; Cricetinae; Cricetulus; Female; Flow Cytometry; Golgi Apparatus; Humans; Mutation; N-Acetylneuraminic Acid; Nucleotide Transport Proteins; Whole Exome Sequencing

Enrichment of mutations in chromatin regulators in people with Rett syndrome lacking mutations in MECP2. - Sajan, Samin A; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; Glaze, Daniel G; Kaufmann, Walter E; Skinner, Steven A; Annese, Fran; Friez, Michael J; Lane, Jane; Percy, Alan K; et al. (Genet Med, 2017)
PURPOSE: Rett syndrome (RTT) is a neurodevelopmental disorder caused primarily by de novo mutations in MECP2 and sometimes in CDKL5 and FOXG1. However, some RTT patients lack mutations in these genes. METHODS: Twenty-two RTT patients without apparent MECP2, CDKL5, and FOXG1 mutations were subjected to both whole-exome sequencing and single-nucleotide polymorphism array-based copy-number variant (CNV) analyses. RESULTS: Three patients had MECP2 mutations initially missed by clinical testing. Of the remaining 19, 17 (89.5%) had 29 other likely pathogenic intragenic mutations and/or CNVs (10 patients had 2 or more). Interestingly, 13 patients had mutations in a gene/region previously reported in other neurodevelopmental disorders (NDDs), thereby providing a potential diagnostic yield of 68.4%. These mutations were significantly enriched in chromatin regulators (corrected P = 0.0068) and moderately enriched in postsynaptic cell membrane molecules (corrected P = 0.076), implicating glutamate receptor signaling. CONCLUSION: The genetic etiology of RTT without MECP2, CDKL5, and FOXG1 mutations is heterogeneous, overlaps with other NDDs, and complicated by a high mutation burden. Dysregulation of chromatin structure and abnormal excitatory synaptic signaling may form two common pathological bases of RTT.Genet Med 19 1, 13-19.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromatin; DNA Copy Number Variations; Female; Forkhead Transcription Factors; Humans; Infant; Male; Methyl-CpG-Binding Protein 2; Mutation; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Rett Syndrome; Whole Exome Sequencing

Evolving health care through personal genomics. - Rehm, Heidi L (Nat Rev Genet, 2017)
With the rapid evolution of next-generation DNA sequencing technologies, the cost of sequencing a human genome has plummeted, and genomics has started to pervade health care across all stages of life - from preconception to adult medicine. Challenges to fully embracing genomics in a clinical setting remain, but some approaches are starting to overcome these barriers, such as community-driven data sharing to improve the accuracy and efficiency of applying genomics to patient care.
Keywords: Adult; Delivery of Health Care; Genetic Testing; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; Precision Medicine

Exome sequencing in Jewish and Arab patients with rhabdomyolysis reveals single-gene etiology in 43% of cases. - Vivante, Asaf; Ityel, Hadas; Pode-Shakked, Ben; Chen, Jing; Shril, Shirlee; van der Ven, Amelie T; Mann, Nina; Schmidt, Johanna Magdalena; Segel, Reeval; Aran, Adi; Zeharia, Avraham; Staretz-Chacham, Orna; et al. (Pediatr Nephrol, 2017)
BACKGROUND: Rhabdomyolysis is a clinical emergency that may cause acute kidney injury (AKI). It can be acquired or due to monogenic mutations. Around 60 different rare monogenic forms of rhabdomyolysis have been reported to date. In the clinical setting, identifying the underlying molecular diagnosis is challenging due to nonspecific presentation, the high number of causative genes, and current lack of data on the prevalence of monogenic forms. METHODS: We employed whole exome sequencing (WES) to reveal the percentage of rhabdomyolysis cases explained by single-gene (monogenic) mutations in one of 58 candidate genes. We investigated a cohort of 21 unrelated families with rhabdomyolysis, in whom no underlying etiology had been previously established. RESULTS: Using WES, we identified causative mutations in candidate genes in nine of the 21 families (43%). We detected disease-causing mutations in eight of 58 candidate genes, grouped into the following categories: (1) disorders of fatty acid metabolism (CPT2), (2) disorders of glycogen metabolism (PFKM and PGAM2), (3) disorders of abnormal skeletal muscle relaxation and contraction (CACNA1S, MYH3, RYR1 and SCN4A), and (4) disorders of purine metabolism (AHCY). CONCLUSIONS: Our findings demonstrate a very high detection rate for monogenic etiologies using WES and reveal broad genetic heterogeneity for rhabdomyolysis. These results highlight the importance of molecular genetic diagnostics for establishing an etiologic diagnosis. Because these patients are at risk for recurrent episodes of rhabdomyolysis and subsequent risk for AKI, WES allows adequate prophylaxis and treatment for these patients and their family members and enables a personalized medicine approach.
Keywords: Adolescent; Adult; Arabs; Child; Exome; Genetic Predisposition to Disease; Humans; Jews; Mutation; Rhabdomyolysis; Whole Exome Sequencing

An exome sequencing study of Moebius syndrome including atypical cases reveals an individual with CFEOM3A and a mutation. - Patel, Ronak M; Liu, David; Gonzaga-Jauregui, Claudia; Jhangiani, Shalini; Lu, James T; Sutton, V Reid; Fernbach, Susan D; Azamian, Mahshid; White, Lisa; Edmond, Jane C; Paysse, Evelyn A; Belmont, John W; et al. (Cold Spring Harb Mol Case Stud, 2017)
Moebius syndrome is characterized by congenital unilateral or bilateral facial and abducens nerve palsies (sixth and seventh cranial nerves) causing facial weakness, feeding difficulties, and restricted ocular movements. Abnormalities of the chest wall such as Poland anomaly and variable limb defects are frequently associated with this syndrome. Most cases are isolated; however, rare families with autosomal dominant transmission with incomplete penetrance and variable expressivity have been described. The genetic basis of this condition remains unknown. In a cohort study of nine individuals suspected to have Moebius syndrome (six typical, three atypical), we performed whole-exome sequencing to try to identify a commonly mutated gene. Although no such gene was identified and we did not find mutations in and , we found a de novo heterozygous mutation, p.E410K, in the gene encoding tubulin beta 3 class III (), in an individual with atypical Moebius syndrome. This individual was diagnosed with near-complete ophthalmoplegia, agenesis of the corpus callosum, and absence of the septum pellucidum. No substantial limb abnormalities were noted. Mutations in have been associated with complex cortical dysplasia and other brain malformations and congenital fibrosis of extraocular muscles type 3A (CFEOM3A). Our report highlights the overlap of genetic etiology and clinical differences between CFEOM and Moebius syndrome and describes our approach to identifying candidate genes for typical and atypical Moebius syndrome.
Keywords: Child; Child, Preschool; Cohort Studies; Exome; Eye Diseases, Hereditary; Facial Paralysis; Female; Humans; Infant; Male; Malformations of Cortical Development; Mobius Syndrome; Muscular Diseases; Mutation; Ocular Motility Disorders; Ophthalmoplegia; Orbital Diseases; Pedigree; Tubulin; Whole Exome Sequencing

Exome-wide Association Study Identifies GREB1L Mutations in Congenital Kidney Malformations. - Sanna-Cherchi, Simone; Khan, Kamal; Westland, Rik; Krithivasan, Priya; Fievet, Lorraine; Rasouly, Hila Milo; Ionita-Laza, Iuliana; Capone, Valentina P; Fasel, David A; Kiryluk, Krzysztof; Kamalakaran, Sitharthan; Bodria, Monica; et al. (Am J Hum Genet, 2017)
Renal agenesis and hypodysplasia (RHD) are major causes of pediatric chronic kidney disease and are highly genetically heterogeneous. We conducted whole-exome sequencing in 202 case subjects with RHD and identified diagnostic mutations in genes known to be associated with RHD in 7/202 case subjects. In an additional affected individual with RHD and a congenital heart defect, we found a homozygous loss-of-function (LOF) variant in SLIT3, recapitulating phenotypes reported with Slit3 inactivation in the mouse. To identify genes associated with RHD, we performed an exome-wide association study with 195 unresolved case subjects and 6,905 control subjects. The top signal resided in GREB1L, a gene implicated previously in Hoxb1 and Shha signaling in zebrafish. The significance of the association, which was p = 2.0 × 10 for novel LOF, increased to p = 4.1 × 10 for LOF and deleterious missense variants combined, and augmented further after accounting for segregation and de novo inheritance of rare variants (joint p = 2.3 × 10). Finally, CRISPR/Cas9 disruption or knockdown of greb1l in zebrafish caused specific pronephric defects, which were rescued by wild-type human GREB1L mRNA, but not mRNA containing alleles identified in case subjects. Together, our study provides insight into the genetic landscape of kidney malformations in humans, presents multiple candidates, and identifies SLIT3 and GREB1L as genes implicated in the pathogenesis of RHD.
Keywords: Alleles; Animals; Case-Control Studies; Clustered Regularly Interspaced Short Palindromic Repeats; Congenital Abnormalities; Exome; Female; Genetic Heterogeneity; Genome-Wide Association Study; Genotype; Heredity; Homozygote; Humans; Kidney; Kidney Diseases; Male; Membrane Proteins; Mice; Mutation; Neoplasm Proteins; Phenotype; RNA, Long Noncoding; Urinary Tract; Urogenital Abnormalities; Zebrafish

An Expanded Multi-Organ Disease Phenotype Associated with Mutations in YARS. - Tracewska-Siemiątkowska, Anna; Haer-Wigman, Lonneke; Bosch, Daniëlle G M; Nickerson, Deborah; Bamshad, Michael J; van de Vorst, Maartje; Rendtorff, Nanna Dahl; Möller, Claes; Kjellström, Ulrika; Andréasson, Sten; Cremers, Frans P M; Tranebjærg, Lisbeth (Genes (Basel), 2017)
Whole exome sequence analysis was performed in a Swedish mother-father-affected proband trio with a phenotype characterized by progressive retinal degeneration with congenital nystagmus, profound congenital hearing impairment, primary amenorrhea, agenesis of the corpus callosum, and liver disease. A homozygous variant c.806T > C, p.(F269S) in the tyrosyl-tRNA synthetase gene () was the only identified candidate variant consistent with autosomal recessive inheritance. Mutations in have previously been associated with both autosomal dominant Charcot-Marie-Tooth syndrome and a recently reported autosomal recessive multiorgan disease. Herein, we propose that mutations in underlie another clinical phenotype adding a second variant of the disease, including retinitis pigmentosa and deafness, to the spectrum of -associated disorders.

First Case of Deficiency in Ecuador, Diagnosed after Whole Exome Sequencing in a Patient with Severe Cutaneous Histoplasmosis. - Pedroza, Luis Alberto; Guerrero, Nina; Stray-Pedersen, Asbjørg; Tafur, Cristina; Macias, Roque; Muñoz, Greta; Akdemir, Zeynep Coban; Jhangiani, Shalini N; Watkin, Levi B; Chinn, Ivan K; Lupski, James R; Orange, Jordan S (Front Pediatr, 2017)
Severe infections with are commonly observed in patient with secondary immunodeficiency disorders. We report a two and a half years old boy previously healthy with disseminated cutaneous histoplasmosis. Using whole exome sequencing, we found an mutation at the gene, suggesting a diagnosis of hyper-IgM (HIGM) syndrome, even in the absence of the usual features for the disease. Interestingly, the patient lives in a region endemic for histoplasmosis. The unusual infections in our case suggest that in children with severe histoplasmosis and resident in endemic areas, HIGM syndrome should be considered as a diagnosis.

Gene-based segregation method for identifying rare variants in family-based sequencing studies. - Qiao, Dandi; Lange, Christoph; Laird, Nan M; Won, Sungho; Hersh, Craig P; Morrow, Jarrett; Hobbs, Brian D; Lutz, Sharon M; Ruczinski, Ingo; Beaty, Terri H; Silverman, Edwin K; Cho, Michael H (Genet Epidemiol, 2017)
Whole-exome sequencing using family data has identified rare coding variants in Mendelian diseases or complex diseases with Mendelian subtypes, using filters based on variant novelty, functionality, and segregation with the phenotype within families. However, formal statistical approaches are limited. We propose a gene-based segregation test (GESE) that quantifies the uncertainty of the filtering approach. It is constructed using the probability of segregation events under the null hypothesis of Mendelian transmission. This test takes into account different degrees of relatedness in families, the number of functional rare variants in the gene, and their minor allele frequencies in the corresponding population. In addition, a weighted version of this test allows incorporating additional subject phenotypes to improve statistical power. We show via simulations that the GESE and weighted GESE tests maintain appropriate type I error rate, and have greater power than several commonly used region-based methods. We apply our method to whole-exome sequencing data from 49 extended pedigrees with severe, early-onset chronic obstructive pulmonary disease (COPD) in the Boston Early-Onset COPD study (BEOCOPD) and identify several promising candidate genes. Our proposed methods show great potential for identifying rare coding variants of large effect and high penetrance for family-based sequencing data. The proposed tests are implemented in an R package that is available on CRAN (https://cran.r-project.org/web/packages/GESE/).
Keywords: Age of Onset; Boston; Computer Simulation; Databases, Genetic; Family; Genetic Variation; Genome, Human; Humans; Models, Genetic; Penetrance; Pulmonary Disease, Chronic Obstructive; Reference Standards; Sequence Analysis, DNA

Genetic Drivers of Kidney Defects in the DiGeorge Syndrome. - Lopez-Rivera, Esther; Liu, Yangfan P; Verbitsky, Miguel; Anderson, Blair R; Capone, Valentina P; Otto, Edgar A; Yan, Zhonghai; Mitrotti, Adele; Martino, Jeremiah; Steers, Nicholas J; Fasel, David A; Vukojevic, Katarina; et al. (N Engl J Med, 2017)
BACKGROUND: The DiGeorge syndrome, the most common of the microdeletion syndromes, affects multiple organs, including the heart, the nervous system, and the kidney. It is caused by deletions on chromosome 22q11.2; the genetic driver of the kidney defects is unknown. METHODS: We conducted a genomewide search for structural variants in two cohorts: 2080 patients with congenital kidney and urinary tract anomalies and 22,094 controls. We performed exome and targeted resequencing in samples obtained from 586 additional patients with congenital kidney anomalies. We also carried out functional studies using zebrafish and mice. RESULTS: We identified heterozygous deletions of 22q11.2 in 1.1% of the patients with congenital kidney anomalies and in 0.01% of population controls (odds ratio, 81.5; P=4.5×10). We localized the main drivers of renal disease in the DiGeorge syndrome to a 370-kb region containing nine genes. In zebrafish embryos, an induced loss of function in snap29, aifm3, and crkl resulted in renal defects; the loss of crkl alone was sufficient to induce defects. Five of 586 patients with congenital urinary anomalies had newly identified, heterozygous protein-altering variants, including a premature termination codon, in CRKL. The inactivation of Crkl in the mouse model induced developmental defects similar to those observed in patients with congenital urinary anomalies. CONCLUSIONS: We identified a recurrent 370-kb deletion at the 22q11.2 locus as a driver of kidney defects in the DiGeorge syndrome and in sporadic congenital kidney and urinary tract anomalies. Of the nine genes at this locus, SNAP29, AIFM3, and CRKL appear to be critical to the phenotype, with haploinsufficiency of CRKL emerging as the main genetic driver. (Funded by the National Institutes of Health and others.).
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Animals; Child; Chromosome Deletion; Chromosomes, Human, Pair 22; DiGeorge Syndrome; Exome; Female; Haploinsufficiency; Heterozygote; Humans; Infant; Infant, Newborn; Kidney; Male; Mice; Models, Animal; Nuclear Proteins; Sequence Analysis, DNA; Urinary Tract; Young Adult; Zebrafish

Genome-Wide Association Studies and Meta-Analyses for Congenital Heart Defects. - Agopian, A J; Goldmuntz, Elizabeth; Hakonarson, Hakon; Sewda, Anshuman; Taylor, Deanne; Mitchell, Laura E (Circ Cardiovasc Genet, 2017)
BACKGROUND: Maternal and inherited (ie, case) genetic factors likely contribute to the pathogenesis of congenital heart defects, but it is unclear whether individual common variants confer a large risk. METHODS AND RESULTS: To evaluate the relationship between individual common maternal/inherited genotypes and risk for heart defects, we conducted genome-wide association studies in 5 cohorts. Three cohorts were recruited at the Children's Hospital of Philadelphia: 670 conotruncal heart defect (CTD) case-parent trios, 317 left ventricular obstructive tract defect (LVOTD) case-parent trios, and 406 CTD cases (n=406) and 2976 pediatric controls. Two cohorts were recruited through the Pediatric Cardiac Genomics Consortium: 355 CTD trios and 192 LVOTD trios. We also conducted meta-analyses using the genome-wide association study results from the CTD cohorts, the LVOTD cohorts, and from the combined CTD and LVOTD cohorts. In the individual genome-wide association studies, several genome-wide significant associations (≤5×10) were observed. In our meta-analyses, 1 genome-wide significant association was detected: the case genotype for rs72820264, an intragenetic single-nucleotide polymorphism associated with LVOTDs (=2.1×10). CONCLUSIONS: We identified 1 novel candidate region associated with LVOTDs and report on several additional regions with suggestive evidence for association with CTD and LVOTD. These studies were constrained by the relatively small samples sizes and thus have limited power to detect small to moderate associations. Approaches that minimize the multiple testing burden (eg, gene or pathway based) may, therefore, be required to uncover common variants contributing to the risk of these relatively rare conditions.
Keywords: Cohort Studies; Databases, Factual; Female; Gene Frequency; Genome-Wide Association Study; Genotype; Heart Defects, Congenital; Humans; Introns; Male; Membrane Proteins; Polymorphism, Single Nucleotide

Germline mutations in ABL1 cause an autosomal dominant syndrome characterized by congenital heart defects and skeletal malformations. - Wang, Xia; Charng, Wu-Lin; Chen, Chun-An; Rosenfeld, Jill A; Al Shamsi, Aisha; Al-Gazali, Lihadh; McGuire, Marianne; Mew, Nicholas Ah; Arnold, Georgianne L; Qu, Chunjing; Ding, Yan; Muzny, Donna M; et al. (Nat Genet, 2017)
ABL1 is a proto-oncogene well known as part of the fusion gene BCR-ABL1 in the Philadelphia chromosome of leukemia cancer cells. Inherited germline ABL1 changes have not been associated with genetic disorders. Here we report ABL1 germline variants cosegregating with an autosomal dominant disorder characterized by congenital heart disease, skeletal abnormalities, and failure to thrive. The variant c.734A>G (p.Tyr245Cys) was found to occur de novo or cosegregate with disease in five individuals (families 1-3). Additionally, a de novo c.1066G>A (p.Ala356Thr) variant was identified in a sixth individual (family 4). We overexpressed the mutant constructs in HEK 293T cells and observed increased tyrosine phosphorylation, suggesting increased ABL1 kinase activities associated with both the p.Tyr245Cys and p.Ala356Thr substitutions. Our clinical and experimental findings, together with previously reported teratogenic effects of selective BCR-ABL inhibitors in humans and developmental defects in Abl1 knockout mice, suggest that ABL1 has an important role during organismal development.
Keywords: Abnormalities, Multiple; Animals; Bone Diseases, Developmental; Cell Line; Chromosome Disorders; Craniofacial Abnormalities; Feeding and Eating Disorders; Female; Fusion Proteins, bcr-abl; Germ-Line Mutation; Heart Defects, Congenital; HEK293 Cells; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Limb Deformities, Congenital; Male; Mice; Mice, Knockout; Philadelphia Chromosome; Phosphorylation; Signal Transduction

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features. - Zhang, Jing; Gambin, Tomasz; Yuan, Bo; Szafranski, Przemyslaw; Rosenfeld, Jill A; Balwi, Mohammed Al; Alswaid, Abdulrahman; Al-Gazali, Lihadh; Shamsi, Aisha M Al; Komara, Makanko; Ali, Bassam R; Roeder, Elizabeth; et al. (Hum Genet, 2017)
Impairment of ubiquitin-proteasome system activity involving ubiquitin ligase genes UBE3A, UBE3B, and HUWE1 and deubiquitinating enzyme genes USP7 and USP9X has been reported in patients with neurodevelopmental delays. To date, only a handful of single-nucleotide variants (SNVs) and copy-number variants (CNVs) involving TRIP12, encoding a member of the HECT domain E3 ubiquitin ligases family on chromosome 2q36.3 have been reported. Using chromosomal microarray analysis and whole-exome sequencing (WES), we have identified, respectively, five deletion CNVs and four inactivating SNVs (two frameshifts, one missense, and one splicing) in TRIP12. Seven of these variants were found to be de novo; parental studies could not be completed in two families. Quantitative PCR analyses of the splicing mutation showed a dramatically decreased level of TRIP12 mRNA in the proband compared to the family controls, indicating a loss-of-function mechanism. The shared clinical features include intellectual disability with or without autistic spectrum disorders, speech delay, and facial dysmorphism. Our findings demonstrate that E3 ubiquitin ligase TRIP12 plays an important role in nervous system development and function. The nine presented pathogenic variants further document that TRIP12 haploinsufficiency causes a childhood-onset neurodevelopmental disorder. Finally, our data enable expansion of the phenotypic spectrum of ubiquitin-proteasome dependent disorders.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Cohort Studies; DNA Copy Number Variations; Facies; Female; Haploinsufficiency; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Ubiquitin-Protein Ligases

Heterozygous De Novo UBTF Gain-of-Function Variant Is Associated with Neurodegeneration in Childhood. - Edvardson, Simon; Nicolae, Claudia M; Agrawal, Pankaj B; Mignot, Cyril; Payne, Katelyn; Prasad, Asuri Narayan; Prasad, Chitra; Sadler, Laurie; Nava, Caroline; Mullen, Thomas E; Begtrup, Amber; Baskin, Berivan; et al. (Am J Hum Genet, 2017)
Ribosomal RNA (rRNA) is transcribed from rDNA by RNA polymerase I (Pol I) to produce the 45S precursor of the 28S, 5.8S, and 18S rRNA components of the ribosome. Two transcription factors have been defined for Pol I in mammals, the selectivity factor SL1, and the upstream binding transcription factor (UBF), which interacts with the upstream control element to facilitate the assembly of the transcription initiation complex including SL1 and Pol I. In seven unrelated affected individuals, all suffering from developmental regression starting at 2.5-7 years, we identified a heterozygous variant, c.628G>A in UBTF, encoding p.Glu210Lys in UBF, which occurred de novo in all cases. While the levels of UBF, Ser388 phosphorylated UBF, and other Pol I-related components (POLR1E, TAF1A, and TAF1C) remained unchanged in cells of an affected individual, the variant conferred gain of function to UBF, manifesting by markedly increased UBF binding to the rDNA promoter and to the 5'- external transcribed spacer. This was associated with significantly increased 18S expression, and enlarged nucleoli which were reduced in number per cell. The data link neurodegeneration in childhood with altered rDNA chromatin status and rRNA metabolism.
Keywords: Adolescent; Adult; Atrophy; Brain; Brain Diseases; Cell Nucleolus; Child; Chromatin; DNA-Binding Proteins; Female; Humans; Male; Neurodegenerative Diseases; Pol1 Transcription Initiation Complex Proteins; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; RNA, Ribosomal, 18S; Young Adult

Heterozygous variants in ACTL6A, encoding a component of the BAF complex, are associated with intellectual disability. - Marom, Ronit; Jain, Mahim; Burrage, Lindsay C; Song, I-Wen; Graham, Brett H; Brown, Chester W; Stevens, Servi J C; Stegmann, Alexander P A; Gunter, Andrew T; Kaplan, Julie D; Gavrilova, Ralitza H; Shinawi, Marwan; et al. (Hum Mutat, 2017)
Pathogenic variants in genes encoding components of the BRG1-associated factor (BAF) chromatin remodeling complex have been associated with intellectual disability syndromes. We identified heterozygous, novel variants in ACTL6A, a gene encoding a component of the BAF complex, in three subjects with varying degrees of intellectual disability. Two subjects have missense variants affecting highly conserved amino acid residues within the actin-like domain. Missense mutations in the homologous region in yeast actin were previously reported to be dominant lethal and were associated with impaired binding of the human ACTL6A to β-actin and BRG1. A third subject has a splicing variant that creates an in-frame deletion. Our findings suggest that the variants identified in our subjects may have a deleterious effect on the function of the protein by disturbing the integrity of the BAF complex. Thus, ACTL6A gene mutation analysis should be considered in patients with intellectual disability, learning disabilities, or developmental language disorder.
Keywords: Actins; Adolescent; Child; Chromatin Assembly and Disassembly; Chromosomal Proteins, Non-Histone; DNA Helicases; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Multiprotein Complexes; Mutation, Missense; Nuclear Proteins; Protein Binding; Transcription Factors

High Rate of Recurrent De Novo Mutations in Developmental and Epileptic Encephalopathies. - Hamdan, Fadi F; Myers, Candace T; Cossette, Patrick; Lemay, Philippe; Spiegelman, Dan; Laporte, Alexandre Dionne; Nassif, Christina; Diallo, Ousmane; Monlong, Jean; Cadieux-Dion, Maxime; Dobrzeniecka, Sylvia; Meloche, Caroline; et al. (Am J Hum Genet, 2017)
Developmental and epileptic encephalopathy (DEE) is a group of conditions characterized by the co-occurrence of epilepsy and intellectual disability (ID), typically with developmental plateauing or regression associated with frequent epileptiform activity. The cause of DEE remains unknown in the majority of cases. We performed whole-genome sequencing (WGS) in 197 individuals with unexplained DEE and pharmaco-resistant seizures and in their unaffected parents. We focused our attention on de novo mutations (DNMs) and identified candidate genes containing such variants. We sought to identify additional subjects with DNMs in these genes by performing targeted sequencing in another series of individuals with DEE and by mining various sequencing datasets. We also performed meta-analyses to document enrichment of DNMs in candidate genes by leveraging our WGS dataset with those of several DEE and ID series. By combining these strategies, we were able to provide a causal link between DEE and the following genes: NTRK2, GABRB2, CLTC, DHDDS, NUS1, RAB11A, GABBR2, and SNAP25. Overall, we established a molecular diagnosis in 63/197 (32%) individuals in our WGS series. The main cause of DEE in these individuals was de novo point mutations (53/63 solved cases), followed by inherited mutations (6/63 solved cases) and de novo CNVs (4/63 solved cases). De novo missense variants explained a larger proportion of individuals in our series than in other series that were primarily ascertained because of ID. Moreover, these DNMs were more frequently recurrent than those identified in ID series. These observations indicate that the genetic landscape of DEE might be different from that of ID without epilepsy.
Keywords: Brain Diseases; Child; Child, Preschool; Epilepsy; Female; Genome, Human; Genome-Wide Association Study; Humans; Intellectual Disability; Male; Mutation; Recurrence; Seizures

Homozygous and hemizygous CNV detection from exome sequencing data in a Mendelian disease cohort. - Gambin, Tomasz; Akdemir, Zeynep C; Yuan, Bo; Gu, Shen; Chiang, Theodore; Carvalho, Claudia M B; Shaw, Chad; Jhangiani, Shalini; Boone, Philip M; Eldomery, Mohammad K; Karaca, Ender; Bayram, Yavuz; et al. (Nucleic Acids Res, 2017)
We developed an algorithm, HMZDelFinder, that uses whole exome sequencing (WES) data to identify rare and intragenic homozygous and hemizygous (HMZ) deletions that may represent complete loss-of-function of the indicated gene. HMZDelFinder was applied to 4866 samples in the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) cohort and detected 773 HMZ deletion calls (567 homozygous or 206 hemizygous) with an estimated sensitivity of 86.5% (82% for single-exonic and 88% for multi-exonic calls) and precision of 78% (53% single-exonic and 96% for multi-exonic calls). Out of 773 HMZDelFinder-detected deletion calls, 82 were subjected to array comparative genomic hybridization (aCGH) and/or breakpoint PCR and 64 were confirmed. These include 18 single-exon deletions out of which 8 were exclusively detected by HMZDelFinder and not by any of seven other CNV detection tools examined. Further investigation of the 64 validated deletion calls revealed at least 15 pathogenic HMZ deletions. Of those, 7 accounted for 17-50% of pathogenic CNVs in different disease cohorts where 7.1-11% of the molecular diagnosis solved rate was attributed to CNVs. In summary, we present an algorithm to detect rare, intragenic, single-exon deletion CNVs using WES data; this tool can be useful for disease gene discovery efforts and clinical WES analyses.
Keywords: Algorithms; Alternative Splicing; Cohort Studies; Computational Biology; Consanguinity; Datasets as Topic; DNA Copy Number Variations; Exome; Genetic Diseases, Inborn; Hemizygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Inheritance Patterns; Models, Genetic; Pedigree; Reproducibility of Results; Sequence Deletion; Workflow

Homozygous Mutations in TBC1D23 Lead to a Non-degenerative Form of Pontocerebellar Hypoplasia. - Marin-Valencia, Isaac; Gerondopoulos, Andreas; Zaki, Maha S; Ben-Omran, Tawfeg; Almureikhi, Mariam; Demir, Ercan; Guemez-Gamboa, Alicia; Gregor, Anne; Issa, Mahmoud Y; Appelhof, Bart; Roosing, Susanne; Musaev, Damir; et al. (Am J Hum Genet, 2017)
Pontocerebellar hypoplasia (PCH) represents a group of recessive developmental disorders characterized by impaired growth of the pons and cerebellum, which frequently follows a degenerative course. Currently, there are 10 partially overlapping clinical subtypes and 13 genes known mutated in PCH. Here, we report biallelic TBC1D23 mutations in six individuals from four unrelated families manifesting a non-degenerative form of PCH. In addition to reduced volume of pons and cerebellum, affected individuals had microcephaly, psychomotor delay, and ataxia. In zebrafish, tbc1d23 morphants replicated the human phenotype showing hindbrain volume loss. TBC1D23 localized at the trans-Golgi and was regulated by the small GTPases Arl1 and Arl8, suggesting a role in trans-Golgi membrane trafficking. Altogether, this study provides a causative link between TBC1D23 mutations and PCH and suggests a less severe clinical course than other PCH subtypes.
Keywords: Adolescent; Animals; Cerebellar Diseases; Child; Child, Preschool; Female; GTPase-Activating Proteins; HeLa Cells; Homozygote; Humans; Male; Microcephaly; Mutation; Pedigree; Phenotype; Zebrafish

Hypogonadotropic Hypogonadism due to Novel FGFR1 Mutations. - Akkuş, Gamze; Kotan, Leman Damla; Durmaz, Erdem; Mengen, Eda; Turan, İhsan; Ulubay, Ayça; Gürbüz, Fatih; Yüksel, Bilgin; Tetiker, Tamer; Topaloğlu, A Kemal (J Clin Res Pediatr Endocrinol, 2017)
OBJECTIVE: The underlying genetic etiology of hypogonadotropic hypogonadism (HH) is heterogeneous. Fibroblast growth factor signaling is pivotal in the ontogeny of gonadotropin-releasing hormone neurons. Loss-of-function mutations in FGFR1 gene cause variable HH phenotypes encompassing pubertal delay to idiopathic HH (IHH) or Kallmann syndrome (KS). As FGFR1 mutations are common, recognizing mutations and associated phenotypes may enhance clinical management. METHODS: Using a candidate gene approach, we screened 52 IHH/KS patients. RESULTS: We identified three novel (IVS3-1G>C and p.W2X, p.R209C) FGFR1 gene mutations. Despite predictive null protein function, patients from the novel mutation families had normosmic IHH without non-reproductive phenotype. CONCLUSION: These findings further emphasize the great variability of FGFR1 mutation phenotypes in IHH/KS.
Keywords: Adolescent; Adult; Family Health; Female; Genetic Predisposition to Disease; Genotype; Humans; Hypogonadism; Klinefelter Syndrome; Male; Mutation; Pedigree; Phenotype; Puberty, Delayed; Receptor, Fibroblast Growth Factor, Type 1; Young Adult

Identification of ASAH1 as a susceptibility gene for familial keloids. - Santos-Cortez, Regie Lyn P; Hu, Ying; Sun, Fanyue; Benahmed-Miniuk, Fairouz; Tao, Jian; Kanaujiya, Jitendra K; Ademola, Samuel; Fadiora, Solomon; Odesina, Victoria; Nickerson, Deborah A; Bamshad, Michael J; Olaitan, Peter B; et al. (Eur J Hum Genet, 2017)
Keloids result from abnormal proliferative scar formation with scar tissue expanding beyond the margin of the original wound and are mostly found in individuals of sub-Saharan African descent. The etiology of keloids has not been resolved but previous studies suggest that keloids are a genetically heterogeneous disorder. Although possible candidate genes have been suggested by genome-wide association studies using common variants, by upregulation in keloids or their involvement in syndromes that include keloid formation, rare coding variants that contribute to susceptibility in non-syndromic keloid formation have not been previously identified. Through analysis of whole-genome data we mapped a locus to chromosome 8p23.3-p21.3 with a statistically significant maximum multipoint LOD score of 4.48. This finding was followed up using exome sequencing and led to the identification of a c.1202T>C (p.(Leu401Pro)) variant in the N-acylsphingosine amidohydrolase (ASAH1) gene that co-segregates with the keloid phenotype in a large Yoruba family. ASAH1 is an acid ceramidase known to be involved in tumor formation by controlling the ratio of ceramide and sphingosine. ASAH1 is also involved in cell proliferation and inflammation, and may affect the development of keloids via multiple mechanisms. Functional studies need to clarify the role of the ASAH1 variant in wound healing.
Keywords: Acid Ceramidase; Adult; Female; Humans; Keloid; Male; Mutation, Missense; Pedigree

Identification of GAA variants through whole exome sequencing targeted to a cohort of 606 patients with unexplained limb-girdle muscle weakness. - Johnson, Katherine; Topf, Ana; Bertoli, Marta; Phillips, Lauren; Claeys, Kristl G; Stojanovic, Vidosava Rakocevic; Perić, Stojan; Hahn, Andreas; Maddison, Paul; Akay, Ela; Bastian, Alexandra E; Łusakowska, Anna; et al. (Orphanet J Rare Dis, 2017)
BACKGROUND: Late-onset Pompe disease is a rare genetic neuromuscular disorder caused by a primary deficiency of α-glucosidase and the associated accumulation of glycogen in lysosomal vacuoles. The deficiency of α-glucosidase can often be detected using an inexpensive and readily accessible dried blood spot test when Pompe disease is suspected. Like several neuromuscular disorders, Pompe disease typically presents with progressive weakness of limb-girdle muscles and respiratory insufficiency. Due to the phenotypic heterogeneity of these disorders, however, it is often difficult for clinicians to reach a diagnosis for patients with Pompe disease. Six hundred and six patients from a European population were recruited onto our study. Inclusion criteria stipulated that index cases must present with limb-girdle weakness or elevated serum creatine kinase activity. Whole exome sequencing with at least 250 ng DNA was completed using an Illumina exome capture and a 38 Mb baited target. A panel of 169 candidate genes for limb-girdle weakness was analysed for disease-causing variants. RESULTS: A total of 35 variants within GAA were detected. Ten distinct variants in eight unrelated index cases (and four siblings not sequenced in our study) were considered disease-causing, with the patients presenting with heterogeneous phenotypes. The eight unrelated individuals were compound heterozygotes for two variants. Six patients carried the intronic splice site c.-13 T > G transversion and two of the six patients also carried the exonic p.Glu176ArgfsTer45 frameshift. Four of the ten variants were novel in their association with Pompe disease. CONCLUSIONS: Here, we highlight the advantage of using whole exome sequencing as a tool for detecting, diagnosing and treating patients with rare, clinically variable genetic disorders.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; alpha-Glucosidases; Child; Child, Preschool; Cohort Studies; Female; Genetic Variation; Glycogen Storage Disease Type II; Humans; Male; Middle Aged; Muscle Weakness; Muscular Dystrophies, Limb-Girdle; Whole Exome Sequencing; Young Adult

Identification of novel candidate disease genes from de novo exonic copy number variants. - Gambin, Tomasz; Yuan, Bo; Bi, Weimin; Liu, Pengfei; Rosenfeld, Jill A; Coban-Akdemir, Zeynep; Pursley, Amber N; Nagamani, Sandesh C S; Marom, Ronit; Golla, Sailaja; Dengle, Lauren; Petrie, Heather G; et al. (Genome Med, 2017)
BACKGROUND: Exon-targeted microarrays can detect small (<1000 bp) intragenic copy number variants (CNVs), including those that affect only a single exon. This genome-wide high-sensitivity approach increases the molecular diagnosis for conditions with known disease-associated genes, enables better genotype-phenotype correlations, and facilitates variant allele detection allowing novel disease gene discovery. METHODS: We retrospectively analyzed data from 63,127 patients referred for clinical chromosomal microarray analysis (CMA) at Baylor Genetics laboratories, including 46,755 individuals tested using exon-targeted arrays, from 2007 to 2017. Small CNVs harboring a single gene or two to five non-disease-associated genes were identified; the genes involved were evaluated for a potential disease association. RESULTS: In this clinical population, among rare CNVs involving any single gene reported in 7200 patients (11%), we identified 145 de novo autosomal CNVs (117 losses and 28 intragenic gains), 257 X-linked deletion CNVs in males, and 1049 inherited autosomal CNVs (878 losses and 171 intragenic gains); 111 known disease genes were potentially disrupted by de novo autosomal or X-linked (in males) single-gene CNVs. Ninety-one genes, either recently proposed as candidate disease genes or not yet associated with diseases, were disrupted by 147 single-gene CNVs, including 37 de novo deletions and ten de novo intragenic duplications on autosomes and 100 X-linked CNVs in males. Clinical features in individuals with de novo or X-linked CNVs encompassing at most five genes (224 bp to 1.6 Mb in size) were compared to those in individuals with larger-sized deletions (up to 5 Mb in size) in the internal CMA database or loss-of-function single nucleotide variants (SNVs) detected by clinical or research whole-exome sequencing (WES). This enabled the identification of recently published genes (BPTF, NONO, PSMD12, TANGO2, and TRIP12), novel candidate disease genes (ARGLU1 and STK3), and further confirmation of disease association for two recently proposed disease genes (MEIS2 and PTCHD1). Notably, exon-targeted CMA detected several pathogenic single-exon CNVs missed by clinical WES analyses. CONCLUSIONS: Together, these data document the efficacy of exon-targeted CMA for detection of genic and exonic CNVs, complementing and extending WES in clinical diagnostics, and the potential for discovery of novel disease genes by genome-wide assay.
Keywords: Cohort Studies; DNA Copy Number Variations; Exons; Genetic Diseases, Inborn; Genome, Human; Homeodomain Proteins; Humans; Intracellular Signaling Peptides and Proteins; Membrane Proteins; Neurodevelopmental Disorders; Protein-Serine-Threonine Kinases; Retrospective Studies; Transcription Factors; Whole Genome Sequencing

Identification of STAC3 variants in non-Native American families with overlapping features of Carey-Fineman-Ziter syndrome and Moebius syndrome. - Telegrafi, Aida; Webb, Bryn D; Robbins, Sarah M; Speck-Martins, Carlos E; FitzPatrick, David; Fleming, Leah; Redett, Richard; Dufke, Andreas; Houge, Gunnar; van Harssel, Jeske J T; Verloes, Alain; Robles, Angela; et al. (Am J Med Genet A, 2017)
Horstick et al. (2013) previously reported a homozygous p.Trp284Ser variant in STAC3 as the cause of Native American myopathy (NAM) in 5 Lumbee Native American families with congenital hypotonia and weakness, cleft palate, short stature, ptosis, kyphoscoliosis, talipes deformities, and susceptibility to malignant hyperthermia (MH). Here we present two non-Native American families, who were found to have STAC3 pathogenic variants. The first proband and her affected older sister are from a consanguineous Qatari family with a suspected clinical diagnosis of Carey-Fineman-Ziter syndrome (CFZS) based on features of hypotonia, myopathic facies with generalized weakness, ptosis, normal extraocular movements, cleft palate, growth delay, and kyphoscoliosis. We identified the homozygous c.851G>C;p.Trp284Ser variant in STAC3 in both sisters. The second proband and his affected sister are from a non-consanguineous, Puerto Rican family who was evaluated for a possible diagnosis of Moebius syndrome (MBS). His features included facial and generalized weakness, minimal limitation of horizontal gaze, cleft palate, and hypotonia, and he has a history of MH. The siblings were identified to be compound heterozygous for STAC3 variants c.851G>C;p.Trp284Ser and c.763_766delCTCT;p.Leu255IlefsX58. Given the phenotypic overlap of individuals with CFZS, MBS, and NAM, we screened STAC3 in 12 individuals diagnosed with CFZS and in 50 individuals diagnosed with MBS or a congenital facial weakness disorder. We did not identify any rare coding variants in STAC3. NAM should be considered in patients presenting with facial and generalized weakness, normal or mildly abnormal extraocular movement, hypotonia, cleft palate, and scoliosis, particularly if there is a history of MH.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Child; Female; Humans; Male; Mobius Syndrome; Muscular Diseases; Mutation; Pedigree; Pierre Robin Syndrome; Prognosis; Young Adult

Improving genetic diagnosis in Mendelian disease with transcriptome sequencing. - Cummings, Beryl B; Marshall, Jamie L; Tukiainen, Taru; Lek, Monkol; Donkervoort, Sandra; Foley, A Reghan; Bolduc, Veronique; Waddell, Leigh B; Sandaradura, Sarah A; O'Grady, Gina L; Estrella, Elicia; Reddy, Hemakumar M; et al. (Sci Transl Med, 2017)
Exome and whole-genome sequencing are becoming increasingly routine approaches in Mendelian disease diagnosis. Despite their success, the current diagnostic rate for genomic analyses across a variety of rare diseases is approximately 25 to 50%. We explore the utility of transcriptome sequencing [RNA sequencing (RNA-seq)] as a complementary diagnostic tool in a cohort of 50 patients with genetically undiagnosed rare muscle disorders. We describe an integrated approach to analyze patient muscle RNA-seq, leveraging an analysis framework focused on the detection of transcript-level changes that are unique to the patient compared to more than 180 control skeletal muscle samples. We demonstrate the power of RNA-seq to validate candidate splice-disrupting mutations and to identify splice-altering variants in both exonic and deep intronic regions, yielding an overall diagnosis rate of 35%. We also report the discovery of a highly recurrent de novo intronic mutation in that results in a dominantly acting splice-gain event, disrupting the critical glycine repeat motif of the triple helical domain. We identify this pathogenic variant in a total of 27 genetically unsolved patients in an external collagen VI-like dystrophy cohort, thus explaining approximately 25% of patients clinically suggestive of having collagen VI dystrophy in whom prior genetic analysis is negative. Overall, this study represents a large systematic application of transcriptome sequencing to rare disease diagnosis and highlights its utility for the detection and interpretation of variants missed by current standard diagnostic approaches.
Keywords: Collagen Type VI; High-Throughput Nucleotide Sequencing; Humans; Muscular Diseases; Mutation; Transcriptome

Intensification: A Resource for Amplifying Population-Genetic Signals with Protein Repeats. - Chen, Jieming; Wang, Bo; Regan, Lynne; Gerstein, Mark (J Mol Biol, 2017)
Large-scale genome sequencing holds great promise for the interpretation of protein structures through the discovery of many, rare functional variants in the human population. However, because protein-coding regions are under high selective constraints, these variants occur at low frequencies, such that there is often insufficient statistics for downstream calculations. To address this problem, we develop the Intensification approach, which uses the modular structure of repeat protein domains to amplify signals of selection from population genetics and traditional interspecies conservation. In particular, we are able to aggregate variants at the codon level to identify important positions in repeat domains that show strong conservation signals. This allows us to compare conservation over different evolutionary timescales. It also enables us to visualize population-genetic measures on protein structures. We make available the Intensification results as an online resource (http://intensification.gersteinlab.org) and illustrate the approach through a case study on the tetratricopeptide repeat.
Keywords: Amino Acid Sequence; Chromosome Mapping; Codon; Computational Biology; Databases, Genetic; Evolution, Molecular; Genetics, Population; Humans; Internet; Molecular Structure; Protein Conformation; Proteins; Signal Processing, Computer-Assisted; X-Rays

International Cooperation to Enable the Diagnosis of All Rare Genetic Diseases. - Boycott, Kym M; Rath, Ana; Chong, Jessica X; Hartley, Taila; Alkuraya, Fowzan S; Baynam, Gareth; Brookes, Anthony J; Brudno, Michael; Carracedo, Angel; den Dunnen, Johan T; Dyke, Stephanie O M; Estivill, Xavier; et al. (Am J Hum Genet, 2017)
Provision of a molecularly confirmed diagnosis in a timely manner for children and adults with rare genetic diseases shortens their "diagnostic odyssey," improves disease management, and fosters genetic counseling with respect to recurrence risks while assuring reproductive choices. In a general clinical genetics setting, the current diagnostic rate is approximately 50%, but for those who do not receive a molecular diagnosis after the initial genetics evaluation, that rate is much lower. Diagnostic success for these more challenging affected individuals depends to a large extent on progress in the discovery of genes associated with, and mechanisms underlying, rare diseases. Thus, continued research is required for moving toward a more complete catalog of disease-related genes and variants. The International Rare Diseases Research Consortium (IRDiRC) was established in 2011 to bring together researchers and organizations invested in rare disease research to develop a means of achieving molecular diagnosis for all rare diseases. Here, we review the current and future bottlenecks to gene discovery and suggest strategies for enabling progress in this regard. Each successful discovery will define potential diagnostic, preventive, and therapeutic opportunities for the corresponding rare disease, enabling precision medicine for this patient population.
Keywords: Databases, Factual; Exome; Genome, Human; Humans; International Cooperation; Rare Diseases

Isolated polycystic liver disease genes define effectors of polycystin-1 function. - Besse, Whitney; Dong, Ke; Choi, Jungmin; Punia, Sohan; Fedeles, Sorin V; Choi, Murim; Gallagher, Anna-Rachel; Huang, Emily B; Gulati, Ashima; Knight, James; Mane, Shrikant; Tahvanainen, Esa; et al. (J Clin Invest, 2017)
Dominantly inherited isolated polycystic liver disease (PCLD) consists of liver cysts that are radiologically and pathologically identical to those seen in autosomal dominant polycystic kidney disease, but without clinically relevant kidney cysts. The causative genes are known for fewer than 40% of PCLD index cases. Here, we have used whole exome sequencing in a discovery cohort of 102 unrelated patients who were excluded for mutations in the 2 most common PCLD genes, PRKCSH and SEC63, to identify heterozygous loss-of-function mutations in 3 additional genes, ALG8, GANAB, and SEC61B. Similarly to PRKCSH and SEC63, these genes encode proteins that are integral to the protein biogenesis pathway in the endoplasmic reticulum. We inactivated these candidate genes in cell line models to show that loss of function of each results in defective maturation and trafficking of polycystin-1, the central determinant of cyst pathogenesis. Despite acting in a common pathway, each PCLD gene product demonstrated distinct effects on polycystin-1 biogenesis. We also found enrichment on a genome-wide basis of heterozygous mutations in the autosomal recessive polycystic kidney disease gene PKHD1, indicating that adult PKHD1 carriers can present with clinical PCLD. These findings define genetic and biochemical modulators of polycystin-1 function and provide a more complete definition of the spectrum of dominant human polycystic diseases.
Keywords: Adult; Animals; Cell Line, Transformed; Cysts; Endoplasmic Reticulum; Female; Genome-Wide Association Study; Glucosidases; Glucosyltransferases; Heterozygote; Humans; Intracellular Signaling Peptides and Proteins; Liver Diseases; Male; Membrane Proteins; Mice; Mutation; SEC Translocation Channels; TRPP Cation Channels

Kaufman oculo-cerebro-facial syndrome in a child with small and absent terminal phalanges and absent nails. - Kariminejad, Ariana; Ajeawung, Norbert Fonya; Bozorgmehr, Bita; Dionne-Laporte, Alexandre; Molidperee, Sirinart; Najafi, Kimia; Gibbs, Richard A; Lee, Brendan H; Hennekam, Raoul C; Campeau, Philippe M (J Hum Genet, 2017)
Kaufman oculo-cerebro-facial syndrome (KOS) is caused by recessive UBE3B mutations and presents with microcephaly, ocular abnormalities, distinctive facial morphology, low cholesterol levels and intellectual disability. We describe a child with microcephaly, brachycephaly, hearing loss, ptosis, blepharophimosis, hypertelorism, cleft palate, multiple renal cysts, absent nails, small or absent terminal phalanges, absent speech and intellectual disability. Syndromes that were initially considered include DOORS syndrome, Coffin-Siris syndrome and Dubowitz syndrome. Clinical investigations coupled with karyotype analysis, array-comparative genomic hybridization, exome and Sanger sequencing were performed to characterize the condition in this child. Sanger sequencing was negative for the DOORS syndrome gene TBC1D24 but exome sequencing identified a homozygous deletion in UBE3B (NM_183415:c.3139_3141del, p.1047_1047del) located within the terminal portion of the HECT domain. This finding coupled with the presence of characteristic features such as brachycephaly, ptosis, blepharophimosis, hypertelorism, short palpebral fissures, cleft palate and developmental delay allowed us to make a diagnosis of KOS. In conclusion, our findings highlight the importance of considering KOS as a differential diagnosis for patients under evaluation for DOORS syndrome and expand the phenotype of KOS to include small or absent terminal phalanges, nails, and the presence of hallux varus and multicystic dysplastic kidneys.
Keywords: Abnormalities, Multiple; Adult; Carrier Proteins; Child; Child, Preschool; Diagnosis, Differential; Eczema; Eye Abnormalities; Face; Facies; Female; Growth Disorders; Hand Deformities, Congenital; Humans; Intellectual Disability; Karyotype; Limb Deformities, Congenital; Male; Microcephaly; Micrognathism; Mutation; Neck; Pathology, Molecular; Sequence Analysis, DNA; Ubiquitin-Protein Ligases

Lessons learned from additional research analyses of unsolved clinical exome cases. - Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Harel, Tamar; Rosenfeld, Jill A; Gambin, Tomasz; Stray-Pedersen, Asbjørg; Küry, Sébastien; Mercier, Sandra; Lessel, Davor; Denecke, Jonas; Wiszniewski, Wojciech; Penney, Samantha; et al. (Genome Med, 2017)
BACKGROUND: Given the rarity of most single-gene Mendelian disorders, concerted efforts of data exchange between clinical and scientific communities are critical to optimize molecular diagnosis and novel disease gene discovery. METHODS: We designed and implemented protocols for the study of cases for which a plausible molecular diagnosis was not achieved in a clinical genomics diagnostic laboratory (i.e. unsolved clinical exomes). Such cases were recruited to a research laboratory for further analyses, in order to potentially: (1) accelerate novel disease gene discovery; (2) increase the molecular diagnostic yield of whole exome sequencing (WES); and (3) gain insight into the genetic mechanisms of disease. Pilot project data included 74 families, consisting mostly of parent-offspring trios. Analyses performed on a research basis employed both WES from additional family members and complementary bioinformatics approaches and protocols. RESULTS: Analysis of all possible modes of Mendelian inheritance, focusing on both single nucleotide variants (SNV) and copy number variant (CNV) alleles, yielded a likely contributory variant in 36% (27/74) of cases. If one includes candidate genes with variants identified within a single family, a potential contributory variant was identified in a total of ~51% (38/74) of cases enrolled in this pilot study. The molecular diagnosis was achieved in 30/63 trios (47.6%). Besides this, the analysis workflow yielded evidence for pathogenic variants in disease-associated genes in 4/6 singleton cases (66.6%), 1/1 multiplex family involving three affected siblings, and 3/4 (75%) quartet families. Both the analytical pipeline and the collaborative efforts between the diagnostic and research laboratories provided insights that allowed recent disease gene discoveries (PURA, TANGO2, EMC1, GNB5, ATAD3A, and MIPEP) and increased the number of novel genes, defined in this study as genes identified in more than one family (DHX30 and EBF3). CONCLUSION: An efficient genomics pipeline in which clinical sequencing in a diagnostic laboratory is followed by the detailed reanalysis of unsolved cases in a research environment, supplemented with WES data from additional family members, and subject to adjuvant bioinformatics analyses including relaxed variant filtering parameters in informatics pipelines, can enhance the molecular diagnostic yield and provide mechanistic insights into Mendelian disorders. Implementing these approaches requires collaborative clinical molecular diagnostic and research efforts.
Keywords: Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; Computational Biology; DNA Copy Number Variations; DNA-Binding Proteins; Exome; Female; Genetic Diseases, Inborn; Genomics; GTP-Binding Protein beta Subunits; Humans; Male; Membrane Proteins; Metalloendopeptidases; Mitochondrial Proteins; Pilot Projects; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Transcription Factors

Loss of Nardilysin, a Mitochondrial Co-chaperone for α-Ketoglutarate Dehydrogenase, Promotes mTORC1 Activation and Neurodegeneration. - Yoon, Wan Hee; Sandoval, Hector; Nagarkar-Jaiswal, Sonal; Jaiswal, Manish; Yamamoto, Shinya; Haelterman, Nele A; Putluri, Nagireddy; Putluri, Vasanta; Sreekumar, Arun; Tos, Tulay; Aksoy, Ayse; Donti, Taraka; et al. (Neuron, 2017)
We previously identified mutations in Nardilysin (dNrd1) in a forward genetic screen designed to isolate genes whose loss causes neurodegeneration in Drosophila photoreceptor neurons. Here we show that NRD1 is localized to mitochondria, where it recruits mitochondrial chaperones and assists in the folding of α-ketoglutarate dehydrogenase (OGDH), a rate-limiting enzyme in the Krebs cycle. Loss of Nrd1 or Ogdh leads to an increase in α-ketoglutarate, a substrate for OGDH, which in turn leads to mTORC1 activation and a subsequent reduction in autophagy. Inhibition of mTOR activity by rapamycin or partially restoring autophagy delays neurodegeneration in dNrd1 mutant flies. In summary, this study reveals a novel role for NRD1 as a mitochondrial co-chaperone for OGDH and provides a mechanistic link between mitochondrial metabolic dysfunction, mTORC1 signaling, and impaired autophagy in neurodegeneration.
Keywords: Animals; Autophagy; Drosophila; Drosophila melanogaster; Drosophila Proteins; Ketoglutarate Dehydrogenase Complex; Ketoglutaric Acids; Lysine; Mechanistic Target of Rapamycin Complex 1; Metalloendopeptidases; Mitochondria; Molecular Chaperones; Multiprotein Complexes; Neurodegenerative Diseases; TOR Serine-Threonine Kinases

Loss-of-Function Mutations in YY1AP1 Lead to Grange Syndrome and a Fibromuscular Dysplasia-Like Vascular Disease. - Guo, Dong-Chuan; Duan, Xue-Yan; Regalado, Ellen S; Mellor-Crummey, Lauren; Kwartler, Callie S; Kim, Dong; Lieberman, Kenneth; de Vries, Bert B A; Pfundt, Rolph; Schinzel, Albert; Kotzot, Dieter; Shen, Xuetong; et al. (Am J Hum Genet, 2017)
Fibromuscular dysplasia (FMD) is a heterogeneous group of non-atherosclerotic and non-inflammatory arterial diseases that primarily involves the renal and cerebrovascular arteries. Grange syndrome is an autosomal-recessive condition characterized by severe and early-onset vascular disease similar to FMD and variable penetrance of brachydactyly, syndactyly, bone fragility, and learning disabilities. Exome-sequencing analysis of DNA from three affected siblings with Grange syndrome identified compound heterozygous nonsense variants in YY1AP1, and homozygous nonsense or frameshift YY1AP1 variants were subsequently identified in additional unrelated probands with Grange syndrome. YY1AP1 encodes yin yang 1 (YY1)-associated protein 1 and is an activator of the YY1 transcription factor. We determined that YY1AP1 localizes to the nucleus and is a component of the INO80 chromatin remodeling complex, which is responsible for transcriptional regulation, DNA repair, and replication. Molecular studies revealed that loss of YY1AP1 in vascular smooth muscle cells leads to cell cycle arrest with decreased proliferation and increased levels of the cell cycle regulator p21/WAF/CDKN1A and disrupts TGF-β-driven differentiation of smooth muscle cells. Identification of YY1AP1 mutations as a cause of FMD indicates that this condition can result from underlying genetic variants that significantly alter the phenotype of vascular smooth muscle cells.
Keywords: Adolescent; Adult; Bone and Bones; Brachydactyly; Cell Cycle Checkpoints; Exome; Female; Fibromuscular Dysplasia; Genes, Recessive; Heterozygote; Homozygote; Humans; Learning Disorders; Male; Middle Aged; Muscle, Smooth, Vascular; Mutation; Nuclear Proteins; Pedigree; Syndactyly; Syndrome; Transcription Factors

Loss-of-Function Variants in MYLK Cause Recessive Megacystis Microcolon Intestinal Hypoperistalsis Syndrome. - Halim, Danny; Brosens, Erwin; Muller, Françoise; Wangler, Michael F; Beaudet, Arthur L; Lupski, James R; Akdemir, Zeynep H Coban; Doukas, Michael; Stoop, Hans J; de Graaf, Bianca M; Brouwer, Rutger W W; van Ijcken, Wilfred F J; et al. (Am J Hum Genet, 2017)
Megacystis microcolon intestinal hypoperistalsis syndrome (MMIHS) is a congenital disorder characterized by loss of smooth muscle contraction in the bladder and intestine. To date, three genes are known to be involved in MMIHS pathogenesis: ACTG2, MYH11, and LMOD1. However, for approximately 10% of affected individuals, the genetic cause of the disease is unknown, suggesting that other loci are most likely involved. Here, we report on three MMIHS-affected subjects from two consanguineous families with no variants in the known MMIHS-associated genes. By performing homozygosity mapping and whole-exome sequencing, we found homozygous variants in myosin light chain kinase (MYLK) in both families. We identified a 7 bp duplication (c.3838_3844dupGAAAGCG [p.Glu1282_Glyfs51]) in one family and a putative splice-site variant (c.3985+5C>A) in the other. Expression studies and splicing assays indicated that both variants affect normal MYLK expression. Because MYLK encodes an important kinase required for myosin activation and subsequent interaction with actin filaments, it is likely that in its absence, contraction of smooth muscle cells is impaired. The existence of a conditional-Mylk-knockout mouse model with severe gut dysmotility and abnormal function of the bladder supports the involvement of this gene in MMIHS pathogenesis. In aggregate, our findings implicate MYLK as a gene involved in the recessive form of MMIHS, confirming that this disease of the visceral organs is heterogeneous with a myopathic origin.
Keywords: Abnormalities, Multiple; Base Sequence; Colon; Female; Genes, Recessive; Homozygote; Humans; Intestinal Pseudo-Obstruction; Male; Mutation; Myosin-Light-Chain Kinase; Pedigree; Urinary Bladder

"Matching" consent to purpose: The example of the Matchmaker Exchange. - Dyke, Stephanie O M; Knoppers, Bartha M; Hamosh, Ada; Firth, Helen V; Hurles, Matthew; Brudno, Michael; Boycott, Kym M; Philippakis, Anthony A; Rehm, Heidi L (Hum Mutat, 2017)
The Matchmaker Exchange (MME) connects rare disease clinicians and researchers to facilitate the sharing of data from undiagnosed patients for the purpose of novel gene discovery. Such sharing raises the odds that two or more similar patients with candidate genes in common may be found, thereby allowing their condition to be more readily studied and understood. Consent considerations for data sharing in MME included both the ethical and legal differences between clinical and research settings and the level of privacy risk involved in sharing varying amounts of rare disease patient data to enable patient matches. In this commentary, we discuss these consent considerations and the resulting MME Consent Policy as they may be relevant to other international data sharing initiatives.
Keywords: Databases, Genetic; Genetic Association Studies; Genetic Diseases, Inborn; Genomics; Humans; Information Dissemination; Patient Selection; Physicians; Rare Diseases; Research Personnel; Translational Medical Research

Matchmaker Exchange. - Sobreira, Nara L M; Arachchi, Harindra; Buske, Orion J; Chong, Jessica X; Hutton, Ben; Foreman, Julia; Schiettecatte, François; Groza, Tudor; Jacobsen, Julius O B; Haendel, Melissa A; Boycott, Kym M; Hamosh, Ada; et al. (Curr Protoc Hum Genet, 2017)
In well over half of the individuals with rare disease who undergo clinical or research next-generation sequencing, the responsible gene cannot be determined. Some reasons for this relatively low yield include unappreciated phenotypic heterogeneity; locus heterogeneity; somatic and germline mosaicism; variants of uncertain functional significance; technically inaccessible areas of the genome; incorrect mode of inheritance investigated; and inadequate communication between clinicians and basic scientists with knowledge of particular genes, proteins, or biological systems. To facilitate such communication and improve the search for patients or model organisms with similar phenotypes and variants in specific candidate genes, we have developed the Matchmaker Exchange (MME). MME was created to establish a federated network connecting databases of genomic and phenotypic data using a common application programming interface (API). To date, seven databases can exchange data using the API (GeneMatcher, PhenomeCentral, DECIPHER, MyGene2, matchbox, Australian Genomics Health Alliance Patient Archive, and Monarch Initiative; the latter included for model organism matching). This article guides usage of the MME for rare disease gene discovery. © 2017 by John Wiley & Sons, Inc.
Keywords: Animals; Computational Biology; Databases, Genetic; Genetic Association Studies; Genetic Predisposition to Disease; Genomics; Humans; Rare Diseases; Software; Web Browser

MED resulting from recessively inherited mutations in the gene encoding calcium-activated nucleotidase CANT1. - Balasubramanian, Karthika; Li, Bing; Krakow, Deborah; Nevarez, Lisette; Ho, Patric J; Ainsworth, Julia A; Nickerson, Deborah A; Bamshad, Michael J; Immken, LaDonna; Lachman, Ralph S; Cohn, Daniel H (Am J Med Genet A, 2017)
Multiple Epiphyseal Dysplasia (MED) is a relatively mild skeletal dysplasia characterized by mild short stature, joint pain, and early-onset osteoarthropathy. Dominantly inherited mutations in COMP, MATN3, COL9A1, COL9A2, and COL9A3, and recessively inherited mutations in SLC26A2, account for the molecular basis of disease in about 80-85% of the cases. In two families with recurrent MED of an unknown molecular basis, we used exome sequencing and candidate gene analysis to identify homozygosity for recessively inherited missense mutations in CANT1, which encodes calcium-activated nucleotidase 1. The MED phenotype is thus allelic to the more severe Desbuquois dysplasia phenotype and the results identify CANT1 as a second locus for recessively inherited MED.
Keywords: Adult; Base Sequence; Child; Child, Preschool; Exome; Female; Genes, Recessive; Humans; Male; Mutation, Missense; Nucleotidases; Osteochondrodysplasias; Pedigree; Radiography

Molecular outcomes, clinical consequences, and genetic diagnosis of Oculocutaneous Albinism in Pakistani population. - Shahzad, Mohsin; Yousaf, Sairah; Waryah, Yar M; Gul, Hadia; Kausar, Tasleem; Tariq, Nabeela; Mahmood, Umair; Ali, Muhammad; Khan, Muzammil A; Waryah, Ali M; Shaikh, Rehan S; Riazuddin, Saima; et al. (Sci Rep, 2017)
Nonsyndromic oculocutaneous Albinism (nsOCA) is clinically characterized by the loss of pigmentation in the skin, hair, and iris. OCA is amongst the most common causes of vision impairment in children. To date, pathogenic variants in six genes have been identified in individuals with nsOCA. Here, we determined the identities, frequencies, and clinical consequences of OCA alleles in 94 previously unreported Pakistani families. Combination of Sanger and Exome sequencing revealed 38 alleles, including 22 novel variants, segregating with nsOCA phenotype in 80 families. Variants of TYR and OCA2 genes were the most common cause of nsOCA, occurring in 43 and 30 families, respectively. Twenty-two novel variants include nine missense, four splice site, two non-sense, one insertion and six gross deletions. In vitro studies revealed retention of OCA proteins harboring novel missense alleles in the endoplasmic reticulum (ER) of transfected cells. Exon-trapping assays with constructs containing splice site alleles revealed errors in splicing. As eight alleles account for approximately 56% (95% CI: 46.52-65.24%) of nsOCA cases, primarily enrolled from Punjab province of Pakistan, hierarchical strategies for variant detection would be feasible and cost-efficient genetic tests for OCA in families with similar origin. Thus, we developed Tetra-primer ARMS assays for rapid, reliable, reproducible and economical screening of most of these common alleles.
Keywords: Albinism, Oculocutaneous; Alleles; Female; Gene Frequency; Humans; Male; Membrane Transport Proteins; Mutation, Missense; Pakistan

Multilevel analyses of SCN5A mutations in arrhythmogenic right ventricular dysplasia/cardiomyopathy suggest non-canonical mechanisms for disease pathogenesis. - Te Riele, Anneline S J M; Agullo-Pascual, Esperanza; James, Cynthia A; Leo-Macias, Alejandra; Cerrone, Marina; Zhang, Mingliang; Lin, Xianming; Lin, Bin; Sobreira, Nara L; Amat-Alarcon, Nuria; Marsman, Roos F; Murray, Brittney; et al. (Cardiovasc Res, 2017)
AIMS: Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy (ARVD/C) is often associated with desmosomal mutations. Recent studies suggest an interaction between the desmosome and sodium channel protein Na1.5. We aimed to determine the prevalence and biophysical properties of mutations in SCN5A (the gene encoding Na1.5) in ARVD/C. METHODS AND RESULTS: We performed whole-exome sequencing in six ARVD/C patients (33% male, 38.2 ± 12.1 years) without a desmosomal mutation. We found a rare missense variant (p.Arg1898His; R1898H) in SCN5A in one patient. We generated induced pluripotent stem cell-derived cardiomyocytes (hIPSC-CMs) from the patient's peripheral blood mononuclear cells. The variant was then corrected (R1898R) using Clustered Regularly Interspaced Short Palindromic Repeats/Cas9 technology, allowing us to study the impact of the R1898H substitution in the same cellular background. Whole-cell patch clamping revealed a 36% reduction in peak sodium current (P = 0.002); super-resolution fluorescence microscopy showed reduced abundance of Na1.5 (P = 0.005) and N-Cadherin (P = 0.026) clusters at the intercalated disc. Subsequently, we sequenced SCN5A in an additional 281 ARVD/C patients (60% male, 34.8 ± 13.7 years, 52% desmosomal mutation-carriers). Five (1.8%) subjects harboured a putatively pathogenic SCN5A variant (p.Tyr416Cys, p.Leu729del, p.Arg1623Ter, p.Ser1787Asn, and p.Val2016Met). SCN5A variants were associated with prolonged QRS duration (119 ± 15 vs. 94 ± 14 ms, P < 0.01) and all SCN5A variant carriers had major structural abnormalities on cardiac imaging. CONCLUSIONS: Almost 2% of ARVD/C patients harbour rare SCN5A variants. For one of these variants, we demonstrated reduced sodium current, Na1.5 and N-Cadherin clusters at junctional sites. This suggests that Na1.5 is in a functional complex with adhesion molecules, and reveals potential non-canonical mechanisms by which Na1.5 dysfunction causes cardiomyopathy.
Keywords: Adult; Antigens, CD; Arrhythmogenic Right Ventricular Dysplasia; Cadherins; Cell Differentiation; CRISPR-Cas Systems; DNA Mutational Analysis; Electrocardiography; Exome; Female; Gene Editing; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Magnetic Resonance Imaging; Male; Membrane Potentials; Middle Aged; Multilevel Analysis; Mutation, Missense; Myocytes, Cardiac; NAV1.5 Voltage-Gated Sodium Channel; Netherlands; Phenotype; Sodium; Transfection; United States; Young Adult

Mutations in ARMC9, which Encodes a Basal Body Protein, Cause Joubert Syndrome in Humans and Ciliopathy Phenotypes in Zebrafish. - Van De Weghe, Julie C; Rusterholz, Tamara D S; Latour, Brooke; Grout, Megan E; Aldinger, Kimberly A; Shaheen, Ranad; Dempsey, Jennifer C; Maddirevula, Sateesh; Cheng, Yong-Han H; Phelps, Ian G; Gesemann, Matthias; Goel, Himanshu; et al. (Am J Hum Genet, 2017)
Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterized by hypotonia, ataxia, abnormal eye movements, and variable cognitive impairment. It is defined by a distinctive brain malformation known as the "molar tooth sign" on axial MRI. Subsets of affected individuals have malformations such as coloboma, polydactyly, and encephalocele, as well as progressive retinal dystrophy, fibrocystic kidney disease, and liver fibrosis. More than 35 genes have been associated with JS, but in a subset of families the genetic cause remains unknown. All of the gene products localize in and around the primary cilium, making JS a canonical ciliopathy. Ciliopathies are unified by their overlapping clinical features and underlying mechanisms involving ciliary dysfunction. In this work, we identify biallelic rare, predicted-deleterious ARMC9 variants (stop-gain, missense, splice-site, and single-exon deletion) in 11 individuals with JS from 8 families, accounting for approximately 1% of the disorder. The associated phenotypes range from isolated neurological involvement to JS with retinal dystrophy, additional brain abnormalities (e.g., heterotopia, Dandy-Walker malformation), pituitary insufficiency, and/or synpolydactyly. We show that ARMC9 localizes to the basal body of the cilium and is upregulated during ciliogenesis. Typical ciliopathy phenotypes (curved body shape, retinal dystrophy, coloboma, and decreased cilia) in a CRISPR/Cas9-engineered zebrafish mutant model provide additional support for ARMC9 as a ciliopathy-associated gene. Identifying ARMC9 mutations as a cause of JS takes us one step closer to a full genetic understanding of this important disorder and enables future functional work to define the central biological mechanisms underlying JS and other ciliopathies.
Keywords: Abnormalities, Multiple; Animals; Armadillo Domain Proteins; Basal Bodies; Base Sequence; Brain; Cerebellum; Cilia; Ciliopathies; Diagnostic Imaging; Exome; Eye Abnormalities; Genetic Predisposition to Disease; Humans; Kidney Diseases, Cystic; Mutation; Phenotype; Retina; Sequence Analysis, DNA; Up-Regulation; Zebrafish; Zebrafish Proteins

Mutations in DYNC2H1, the cytoplasmic dynein 2, heavy chain 1 motor protein gene, cause short-rib polydactyly type I, Saldino-Noonan type. - Badiner, N; Taylor, S P; Forlenza, K; Lachman, R S; Bamshad, M; Nickerson, D; Cohn, D H; Krakow, D (Clin Genet, 2017)
The short-rib polydactyly syndromes (SRPS) are autosomal recessively inherited, genetically heterogeneous skeletal ciliopathies. SRPS phenotypes were historically categorized as types I-IV, with type I first delineated by Saldino and Noonan in 1972. Characteristic findings among all forms of SRP include short horizontal ribs, short limbs and polydactyly. The SRP type I phenotype is characterized by a very small thorax, extreme micromelia, very short, poorly mineralized long bones, and multiple organ system anomalies. To date, the molecular basis of this most severe type of SRP, also known as Saldino-Noonan syndrome, has not been determined. We identified three SRP cases that fit the original phenotypic description of SRP type I. In all three cases, exome sequence analysis revealed compound heterozygosity for mutations in DYNC2H1, which encodes the main component of the retrograde IFT A motor, cytoplasmic dynein 2 heavy chain 1. Thus SRP type I, II, III and asphyxiating thoracic dystrophy (ATD), which also result from DYNC2H1 mutations. Herein we describe the phenotypic features, radiographic findings, and molecular basis of SRP type I.
Keywords: Cytoplasmic Dyneins; Ellis-Van Creveld Syndrome; Female; Fetus; Genetic Heterogeneity; Genetic Predisposition to Disease; Humans; Infant, Newborn; Mutation; Phenotype; Pregnancy; Radiography; Short Rib-Polydactyly Syndrome; Whole Exome Sequencing

Mutations in EBF3 Disturb Transcriptional Profiles and Cause Intellectual Disability, Ataxia, and Facial Dysmorphism. - Harms, Frederike Leonie; Girisha, Katta M; Hardigan, Andrew A; Kortüm, Fanny; Shukla, Anju; Alawi, Malik; Dalal, Ashwin; Brady, Lauren; Tarnopolsky, Mark; Bird, Lynne M; Ceulemans, Sophia; Bebin, Martina; et al. (Am J Hum Genet, 2017)
From a GeneMatcher-enabled international collaboration, we identified ten individuals affected by intellectual disability, speech delay, ataxia, and facial dysmorphism and carrying a deleterious EBF3 variant detected by whole-exome sequencing. One 9-bp duplication and one splice-site, five missense, and two nonsense variants in EBF3 were found; the mutations occurred de novo in eight individuals, and the missense variant c.625C>T (p.Arg209Trp) was inherited by two affected siblings from their healthy mother, who is mosaic. EBF3 belongs to the early B cell factor family (also known as Olf, COE, or O/E) and is a transcription factor involved in neuronal differentiation and maturation. Structural assessment predicted that the five amino acid substitutions have damaging effects on DNA binding of EBF3. Transient expression of EBF3 mutant proteins in HEK293T cells revealed mislocalization of all but one mutant in the cytoplasm, as well as nuclear localization. By transactivation assays, all EBF3 mutants showed significantly reduced or no ability to activate transcription of the reporter gene CDKN1A, and in situ subcellular fractionation experiments demonstrated that EBF3 mutant proteins were less tightly associated with chromatin. Finally, in RNA-seq and ChIP-seq experiments, EBF3 acted as a transcriptional regulator, and mutant EBF3 had reduced genome-wide DNA binding and gene-regulatory activity. Our findings demonstrate that variants disrupting EBF3-mediated transcriptional regulation cause intellectual disability and developmental delay and are present in ∼0.1% of individuals with unexplained neurodevelopmental disorders.
Keywords: Adolescent; Adult; Amino Acid Substitution; Ataxia; Child; Child, Preschool; Chromatin; Cyclin-Dependent Kinase Inhibitor p21; Developmental Disabilities; Exome; Face; Female; Gene Expression Regulation; Genes, Reporter; HEK293 Cells; Humans; Intellectual Disability; Language Development Disorders; Male; Models, Molecular; Mosaicism; Mutation; Neurodevelopmental Disorders; Protein Transport; Syndrome; Transcription Factors; Transcription, Genetic

Mutations in Fibronectin Cause a Subtype of Spondylometaphyseal Dysplasia with "Corner Fractures". - Lee, Chae Syng; Fu, He; Baratang, Nissan; Rousseau, Justine; Kumra, Heena; Sutton, V Reid; Niceta, Marcello; Ciolfi, Andrea; Yamamoto, Guilherme; Bertola, Débora; Marcelis, Carlo L; Lugtenberg, Dorien; et al. (Am J Hum Genet, 2017)
Fibronectin is a master organizer of extracellular matrices (ECMs) and promotes the assembly of collagens, fibrillin-1, and other proteins. It is also known to play roles in skeletal tissues through its secretion by osteoblasts, chondrocytes, and mesenchymal cells. Spondylometaphyseal dysplasias (SMDs) comprise a diverse group of skeletal dysplasias and often manifest as short stature, growth-plate irregularities, and vertebral anomalies, such as scoliosis. By comparing the exomes of individuals with SMD with the radiographic appearance of "corner fractures" at metaphyses, we identified three individuals with fibronectin (FN1) variants affecting highly conserved residues. Furthermore, using matching tools and the SkelDys emailing list, we identified other individuals with de novo FN1 variants and a similar phenotype. The severe scoliosis in most individuals and rare developmental coxa vara distinguish individuals with FN1 mutations from those with classical Sutcliffe-type SMD. To study functional consequences of these FN1 mutations on the protein level, we introduced three disease-associated missense variants (p.Cys87Phe [c.260G>T], p.Tyr240Asp [c.718T>G], and p.Cys260Gly [c.778T>G]) into a recombinant secreted N-terminal 70 kDa fragment (rF70K) and the full-length fibronectin (rFN). The wild-type rF70K and rFN were secreted into the culture medium, whereas all mutant proteins were either not secreted or secreted at significantly lower amounts. Immunofluorescence analysis demonstrated increased intracellular retention of the mutant proteins. In summary, FN1 mutations that cause defective fibronectin secretion are found in SMD, and we thus provide additional evidence for a critical function of fibronectin in cartilage and bone.
Keywords: Adolescent; Adult; Bone and Bones; Bone Diseases, Developmental; Cartilage; Child; Child, Preschool; Exome; Female; Fibronectins; Fractures, Bone; Humans; Male; Mutation; Osteochondrodysplasias; Phenotype; Scoliosis

Mutations in GPAA1, Encoding a GPI Transamidase Complex Protein, Cause Developmental Delay, Epilepsy, Cerebellar Atrophy, and Osteopenia. - Nguyen, Thi Tuyet Mai; Murakami, Yoshiko; Sheridan, Eamonn; Ehresmann, Sophie; Rousseau, Justine; St-Denis, Anik; Chai, Guoliang; Ajeawung, Norbert F; Fairbrother, Laura; Reimschisel, Tyler; Bateman, Alexandra; Berry-Kravis, Elizabeth; et al. (Am J Hum Genet, 2017)
Approximately one in every 200 mammalian proteins is anchored to the cell membrane through a glycosylphosphatidylinositol (GPI) anchor. These proteins play important roles notably in neurological development and function. To date, more than 20 genes have been implicated in the biogenesis of GPI-anchored proteins. GPAA1 (glycosylphosphatidylinositol anchor attachment 1) is an essential component of the transamidase complex along with PIGK, PIGS, PIGT, and PIGU (phosphatidylinositol-glycan biosynthesis classes K, S, T, and U, respectively). This complex orchestrates the attachment of the GPI anchor to the C terminus of precursor proteins in the endoplasmic reticulum. Here, we report bi-allelic mutations in GPAA1 in ten individuals from five families. Using whole-exome sequencing, we identified two frameshift mutations (c.981_993del [p.Gln327Hisfs102] and c.920delG [p.Gly307Alafs11]), one intronic splicing mutation (c.1164+5C>T), and six missense mutations (c.152C>T [p.Ser51Leu], c.160_161delinsAA [p.Ala54Asn], c.527G>C [p.Trp176Ser], c.869T>C [p.Leu290Pro], c.872T>C [p.Leu291Pro], and c.1165G>C [p.Ala389Pro]). Most individuals presented with global developmental delay, hypotonia, early-onset seizures, cerebellar atrophy, and osteopenia. The splicing mutation was found to decrease GPAA1 mRNA. Moreover, flow-cytometry analysis of five available individual samples showed that several GPI-anchored proteins had decreased cell-surface abundance in leukocytes (FLAER, CD16, and CD59) or fibroblasts (CD73 and CD109). Transduction of fibroblasts with a lentivirus encoding the wild-type protein partially rescued the deficiency of GPI-anchored proteins. These findings highlight the role of the transamidase complex in the development and function of the cerebellum and the skeletal system.
Keywords: Acyltransferases; Adolescent; Adult; Alleles; Atrophy; Bone Diseases, Metabolic; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Epilepsy; Exome; Female; Fibroblasts; Glycosylphosphatidylinositols; Humans; Male; Membrane Glycoproteins; Muscle Hypotonia; Mutation; Pedigree; RNA, Messenger; Seizures

Mutations in IFT-A satellite core component genes and produce short rib polydactyly syndrome with distinctive campomelia. - Duran, Ivan; Taylor, S Paige; Zhang, Wenjuan; Martin, Jorge; Qureshi, Faisal; Jacques, Suzanne M; Wallerstein, Robert; Lachman, Ralph S; Nickerson, Deborah A; Bamshad, Michael; Cohn, Daniel H; Krakow, Deborah (Cilia, 2017)
BACKGROUND: Skeletal ciliopathies comprise a spectrum of ciliary malfunction disorders that have a profound effect on the skeleton. Most common among these disorders is short rib polydactyly syndrome (SRPS), a recessively inherited perinatal lethal condition characterized by a long narrow chest, markedly shortened long bones, polydactyly and, often, multi-organ system involvement. SRPS shows extensive locus heterogeneity with mutations in genes encoding proteins that participate in cilia formation and/or function. RESULTS: Herein we describe mutations in , a satellite member of the retrograde IFT-A complex, that produce a form of SRPS with unusual bending of the ribs and appendicular bones. These newly described mutations disrupted cilia formation, produced abnormalities in cartilage growth plate architecture thus contributing to altered endochondral ossification. We further show that the SRPS phenotype is similar to SRPS resulting from mutations in the gene encoding IFT121 (WDR35), a direct interactor with IFT43. CONCLUSIONS: This study defines a new -associated phenotype, identifying an additional locus for SRPS. The data demonstrate that IFT43 is essential for ciliogenesis and that the mutations disrupted the orderly proliferation and differentiation of growth plate chondrocytes, resulting in a severe effect on endochondral ossification and mineralization. Phenotypic similarities with SRPS cases resulting from mutations in the gene encoding the IFT43 direct interacting protein IFT121 suggests that similar mechanisms may be disrupted by defects in these two IFT-A satellite interactors.

Mutations in KDSR Cause Recessive Progressive Symmetric Erythrokeratoderma. - Boyden, Lynn M; Vincent, Nicholas G; Zhou, Jing; Hu, Ronghua; Craiglow, Brittany G; Bayliss, Susan J; Rosman, Ilana S; Lucky, Anne W; Diaz, Luis A; Goldsmith, Lowell A; Paller, Amy S; Lifton, Richard P; et al. (Am J Hum Genet, 2017)
The discovery of new genetic determinants of inherited skin disorders has been instrumental to the understanding of epidermal function, differentiation, and renewal. Here, we show that mutations in KDSR (3-ketodihydrosphingosine reductase), encoding an enzyme in the ceramide synthesis pathway, lead to a previously undescribed recessive Mendelian disorder in the progressive symmetric erythrokeratoderma spectrum. This disorder is characterized by severe lesions of thick scaly skin on the face and genitals and thickened, red, and scaly skin on the hands and feet. Although exome sequencing revealed several of the KDSR mutations, we employed genome sequencing to discover a pathogenic 346 kb inversion in multiple probands, and cDNA sequencing and a splicing assay established that two mutations, including a recurrent silent third base change, cause exon skipping. Immunohistochemistry and yeast complementation studies demonstrated that the mutations cause defects in KDSR function. Systemic isotretinoin therapy has achieved nearly complete resolution in the two probands in whom it has been applied, consistent with the effects of retinoic acid on alternative pathways for ceramide generation.
Keywords: Alcohol Oxidoreductases; Ceramides; Genes, Recessive; Genetic Complementation Test; Genetic Predisposition to Disease; Heterozygote; Humans; Intermediate Filament Proteins; Keratosis; Mutation; Polymorphism, Single Nucleotide; RNA Splicing; Saccharomyces cerevisiae

Mutations in KEOPS-complex genes cause nephrotic syndrome with primary microcephaly. - Braun, Daniela A; Rao, Jia; Mollet, Geraldine; Schapiro, David; Daugeron, Marie-Claire; Tan, Weizhen; Gribouval, Olivier; Boyer, Olivia; Revy, Patrick; Jobst-Schwan, Tilman; Schmidt, Johanna Magdalena; Lawson, Jennifer A; et al. (Nat Genet, 2017)
Galloway-Mowat syndrome (GAMOS) is an autosomal-recessive disease characterized by the combination of early-onset nephrotic syndrome (SRNS) and microcephaly with brain anomalies. Here we identified recessive mutations in OSGEP, TP53RK, TPRKB, and LAGE3, genes encoding the four subunits of the KEOPS complex, in 37 individuals from 32 families with GAMOS. CRISPR-Cas9 knockout in zebrafish and mice recapitulated the human phenotype of primary microcephaly and resulted in early lethality. Knockdown of OSGEP, TP53RK, or TPRKB inhibited cell proliferation, which human mutations did not rescue. Furthermore, knockdown of these genes impaired protein translation, caused endoplasmic reticulum stress, activated DNA-damage-response signaling, and ultimately induced apoptosis. Knockdown of OSGEP or TP53RK induced defects in the actin cytoskeleton and decreased the migration rate of human podocytes, an established intermediate phenotype of SRNS. We thus identified four new monogenic causes of GAMOS, describe a link between KEOPS function and human disease, and delineate potential pathogenic mechanisms.
Keywords: Animals; Apoptosis; Carrier Proteins; Cell Movement; CRISPR-Cas Systems; Cytoskeleton; DNA Repair; Endoplasmic Reticulum Stress; Gene Knockout Techniques; Hernia, Hiatal; Humans; Intracellular Signaling Peptides and Proteins; Metalloendopeptidases; Mice; Microcephaly; Models, Molecular; Multiprotein Complexes; Mutation; Nephrosis; Nephrotic Syndrome; Podocytes; Protein Conformation; Protein-Serine-Threonine Kinases; RNA Processing, Post-Transcriptional; RNA, Transfer; Telomere Homeostasis; Zebrafish; Zebrafish Proteins

Mutations in sphingosine-1-phosphate lyase cause nephrosis with ichthyosis and adrenal insufficiency. - Lovric, Svjetlana; Goncalves, Sara; Gee, Heon Yung; Oskouian, Babak; Srinivas, Honnappa; Choi, Won-Il; Shril, Shirlee; Ashraf, Shazia; Tan, Weizhen; Rao, Jia; Airik, Merlin; Schapiro, David; et al. (J Clin Invest, 2017)
Steroid-resistant nephrotic syndrome (SRNS) causes 15% of chronic kidney disease cases. A mutation in 1 of over 40 monogenic genes can be detected in approximately 30% of individuals with SRNS whose symptoms manifest before 25 years of age. However, in many patients, the genetic etiology remains unknown. Here, we have performed whole exome sequencing to identify recessive causes of SRNS. In 7 families with SRNS and facultative ichthyosis, adrenal insufficiency, immunodeficiency, and neurological defects, we identified 9 different recessive mutations in SGPL1, which encodes sphingosine-1-phosphate (S1P) lyase. All mutations resulted in reduced or absent SGPL1 protein and/or enzyme activity. Overexpression of cDNA representing SGPL1 mutations resulted in subcellular mislocalization of SGPL1. Furthermore, expression of WT human SGPL1 rescued growth of SGPL1-deficient dpl1Δ yeast strains, whereas expression of disease-associated variants did not. Immunofluorescence revealed SGPL1 expression in mouse podocytes and mesangial cells. Knockdown of Sgpl1 in rat mesangial cells inhibited cell migration, which was partially rescued by VPC23109, an S1P receptor antagonist. In Drosophila, Sply mutants, which lack SGPL1, displayed a phenotype reminiscent of nephrotic syndrome in nephrocytes. WT Sply, but not the disease-associated variants, rescued this phenotype. Together, these results indicate that SGPL1 mutations cause a syndromic form of SRNS.
Keywords: Aldehyde-Lyases; Animals; Cell Line; Cell Movement; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Ichthyosis, Lamellar; Male; Mesangial Cells; Mice; Mice, Knockout; Mutation; Nephrotic Syndrome; Protein Transport; Rats

My46: a Web-based tool for self-guided management of genomic test results in research and clinical settings. - Tabor, Holly K; Jamal, Seema M; Yu, Joon-Ho; Crouch, Julia M; Shankar, Aditi G; Dent, Karin M; Anderson, Nick; Miller, Damon A; Futral, Brett T; Bamshad, Michael J (Genet Med, 2017)
A major challenge to implementing precision medicine is the need for an efficient and cost-effective strategy for returning individual genomic test results that is easily scalable and can be incorporated into multiple models of clinical practice. My46 is a Web-based tool for managing the return of genetic results that was designed and developed to support a wide range of approaches to disclosing results, ranging from traditional face-to-face disclosure to self-guided models. My46 has five key functions: set and modify results-return preferences, return results, educate, manage the return of results, and assess the return of results. These key functions are supported by six distinct modules and a suite of features that enhance the user experience, ease site navigation, facilitate knowledge sharing, and enable results-return tracking. My46 is a potentially effective solution for returning results and supports current trends toward shared decision making between patients and providers and patient-driven health management.Genet Med 19 4, 467-475.
Keywords: Biomedical Research; Computational Biology; Decision Making; Genomics; Humans; Internet; Medical Informatics; Patient Access to Records; Precision Medicine

Neonatal fractures as a presenting feature of LMOD3-associated congenital myopathy. - Abbott, Megan; Jain, Mahim; Pferdehirt, Rachel; Chen, Yuqing; Tran, Alyssa; Duz, Mehmet B; Seven, Mehmet; Gibbs, Richard A; Muzny, Donna; Lee, Brendan; Marom, Ronit; Burrage, Lindsay C (Am J Med Genet A, 2017)
Nemaline myopathy is a rare inherited disorder characterized by weakness, hypotonia, and depressed deep tendon reflexes. It is clinically and genetically heterogeneous, with the most severe phenotype presenting as perinatal akinesia, severe muscle weakness, feeding difficulties and respiratory failure, leading to early mortality. Pathogenic variants in 12 genes, encoding components of the sarcomere or factors related to myogenesis, have been reported in patients affected with the disorder. Here, we describe an early, lethal presentation of decreased fetal movements, hypotonia, muscle weakness, and neonatal respiratory failure requiring ventilator support in three siblings from a consanguineous family. All exhibited perinatal fractures, and thus, a skeletal dysplasia was considered as possibly contributing to the phenotype. However, whole exome sequencing revealed a homozygous, loss-of-function pathogenic variant in LMOD3, which has recently been associated with nemaline myopathy and, in a subset of patients, perinatal fractures. This case demonstrates the importance of considering congenital neuromuscular disorders in the differential diagnosis of perinatal fractures.
Keywords: Female; Fractures, Bone; Homozygote; Humans; Infant, Newborn; Male; Muscle Proteins; Mutation; Myopathies, Structural, Congenital; Pedigree

Novel Genetic Triggers and Genotype-Phenotype Correlations in Patients With Left Ventricular Noncompaction. - Miszalski-Jamka, Karol; Jefferies, John L; Mazur, Wojciech; Głowacki, Jan; Hu, Jianhong; Lazar, Monika; Gibbs, Richard A; Liczko, Jacek; Kłyś, Jan; Venner, Eric; Muzny, Donna M; Rycaj, Jarosław; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Left ventricular noncompaction (LVNC) is a genetically and phenotypically heterogeneous disease and, although increasingly recognized in clinical practice, there is a lack of widely accepted diagnostic criteria. We sought to identify novel genetic causes of LVNC and describe genotype-phenotype correlations. METHODS AND RESULTS: A total of 190 patients from 174 families with left ventricular hypertrabeculation (LVHT) or LVNC were referred for cardiac magnetic resonance and whole-exome sequencing. A total of 425 control individuals were included to identify variants of interest (VOIs). We found an excess of 138 VOIs in 102 (59%) unrelated patients in 54 previously identified LVNC or other known cardiomyopathy genes. VOIs were found in 68 of 90 probands with LVNC and 34 of 84 probands with LVHT (76% and 40%, respectively; <0.001). We identified 0, 1, and ≥2 VOIs in 72, 74, and 28 probands, respectively. We found increasing number of VOIs in a patient strongly correlated with several markers of disease severity, including ratio of noncompacted to compacted myocardium (<0.001) and left ventricular ejection fraction (=0.01). The presence of sarcomeric gene mutations was associated with increased occurrence of late gadolinium enhancement (=0.004). CONCLUSIONS: LVHT and LVNC likely represent a continuum of genotypic disease with differences in severity and variable phenotype explained, in part, by the number of VOIs and whether mutations are present in sarcomeric or nonsarcomeric genes. Presence of VOIs is common in patients with LVHT. Our findings expand the current clinical and genetic diagnostic approaches for patients with LVHT and LVNC.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Aged; Cardiac Myosins; Carrier Proteins; Child; Connectin; Female; Genetic Association Studies; Genetic Variation; Heart Ventricles; Humans; LIM Domain Proteins; Magnetic Resonance Imaging, Cine; Male; Middle Aged; Muscle Proteins; Myocardium; Myosin Heavy Chains; Prospective Studies; Severity of Illness Index; Tropomyosin; Ventricular Dysfunction, Left; Young Adult

A novel mutation in GMPPA in siblings with apparent intellectual disability, epilepsy, dysmorphism, and autonomic dysfunction. - Gold, Wendy A; Sobreira, Nara; Wiame, Elsa; Marbaix, Alexandre; Van Schaftingen, Emile; Franzka, Patricia; Riley, Lisa G; Worgan, Lisa; Hübner, Christian A; Christodoulou, John; Adès, Lesley C (Am J Med Genet A, 2017)
GMPPA encodes the GDP-mannose pyrophosphorylase A protein (GMPPA). The function of GMPPA is not well defined, however it is a homolog of GMPPB which catalyzes the reaction that converts mannose-1-phosphate and guanosine-5'-triphosphate to GDP-mannose. Previously, biallelic mutations in GMPPA were reported to cause a disorder characterized by achalasia, alacrima, neurological deficits, and intellectual disability. In this study, we report a female proband with achalasia, alacrima, hypohydrosis, apparent intellectual disability, seizures, microcephaly, esotropia, and craniofacial dysmorphism. Exome sequencing identified a previously unreported homozygous c.853+1G>A variant in GMPPA in the proband and her affected sister. Their unaffected parents were heterozygous, and unaffected brother homozygous wild type for this variant. Lymphoblast cells from the affected sisters showed complete loss of the GMPPA protein by Western blotting, and increased levels of GDP-mannose in lymphoblasts on high performance liquid chromatography. Based on our findings and the previous report describing patients with an overlapping phenotype, we conclude that this novel variant in GMPPA, identified by exome sequencing in the proband and her affected sister, is the genetic cause of their phenotype and may expand the known phenotype of this recently described glycosylation disorder.
Keywords: Abnormalities, Multiple; Child; Child, Preschool; Craniofacial Abnormalities; Epilepsy; Exome; Facies; Female; Heterozygote; Humans; Intellectual Disability; Microcephaly; Muscular Atrophy; Mutation, Missense; Nucleotidyltransferases; Pedigree; Phenotype; Seizures

An Organismal CNV Mutator Phenotype Restricted to Early Human Development. - Liu, Pengfei; Yuan, Bo; Carvalho, Claudia M B; Wuster, Arthur; Walter, Klaudia; Zhang, Ling; Gambin, Tomasz; Chong, Zechen; Campbell, Ian M; Coban Akdemir, Zeynep; Gelowani, Violet; Writzl, Karin; et al. (Cell, 2017)
De novo copy number variants (dnCNVs) arising at multiple loci in a personal genome have usually been considered to reflect cancer somatic genomic instabilities. We describe a multiple dnCNV (MdnCNV) phenomenon in which individuals with genomic disorders carry five to ten constitutional dnCNVs. These CNVs originate from independent formation incidences, are predominantly tandem duplications or complex gains, exhibit breakpoint junction features reminiscent of replicative repair, and show increased de novo point mutations flanking the rearrangement junctions. The active CNV mutation shower appears to be restricted to a transient perizygotic period. We propose that a defect in the CNV formation process is responsible for the "CNV-mutator state," and this state is dampened after early embryogenesis. The constitutional MdnCNV phenomenon resembles chromosomal instability in various cancers. Investigations of this phenomenon may provide unique access to understanding genomic disorders, structural variant mutagenesis, human evolution, and cancer biology.
Keywords: Chromosome Aberrations; Chromosome Breakpoints; Chromosome Duplication; DNA Copy Number Variations; DNA Replication; Embryonic Development; Female; Gametogenesis; Genetic Diseases, Inborn; Genomic Instability; Humans; Male; Mutation

P4HA1 mutations cause a unique congenital disorder of connective tissue involving tendon, bone, muscle and the eye. - Zou, Yaqun; Donkervoort, Sandra; Salo, Antti M; Foley, A Reghan; Barnes, Aileen M; Hu, Ying; Makareeva, Elena; Leach, Meganne E; Mohassel, Payam; Dastgir, Jahannaz; Deardorff, Matthew A; Cohn, Ronald D; et al. (Hum Mol Genet, 2017)
Collagen prolyl 4-hydroxylases (C-P4Hs) play a central role in the formation and stabilization of the triple helical domain of collagens. P4HA1 encodes the catalytic α(I) subunit of the main C-P4H isoenzyme (C-P4H-I). We now report human bi-allelic P4HA1 mutations in a family with a congenital-onset disorder of connective tissue, manifesting as early-onset joint hypermobility, joint contractures, muscle weakness and bone dysplasia as well as high myopia, with evidence of clinical improvement of motor function over time in the surviving patient. Similar to P4ha1 null mice, which die prenatally, the muscle tissue from P1 and P2 was found to have reduced collagen IV immunoreactivity at the muscle basement membrane. Patients were compound heterozygous for frameshift and splice site mutations leading to reduced, but not absent, P4HA1 protein level and C-P4H activity in dermal fibroblasts compared to age-matched control samples. Differential scanning calorimetry revealed reduced thermal stability of collagen in patient-derived dermal fibroblasts versus age-matched control samples. Mutations affecting the family of C-P4Hs, and in particular C-P4H-I, should be considered in patients presenting with congenital connective tissue/myopathy overlap disorders with joint hypermobility, contractures, mild skeletal dysplasia and high myopia.
Keywords: Animals; Basement Membrane; Bone and Bones; Child; Collagen Type IV; Connective Tissue; Humans; Male; Mice; Mice, Knockout; Muscles; Mutation; Osteochondrodysplasias; Procollagen-Proline Dioxygenase; Prolyl Hydroxylases; Tendons

Patients with a Kabuki syndrome phenotype demonstrate DNA methylation abnormalities. - Sobreira, Nara; Brucato, Martha; Zhang, Li; Ladd-Acosta, Christine; Ongaco, Chrissie; Romm, Jane; Doheny, Kimberly F; Mingroni-Netto, Regina C; Bertola, Débora; Kim, Chong A; Perez, Ana Ba; Melaragno, Maria I; et al. (Eur J Hum Genet, 2017)
Kabuki syndrome is a monogenic disorder caused by loss of function variants in either of two genes encoding histone-modifying enzymes. We performed targeted sequencing in a cohort of 27 probands with a clinical diagnosis of Kabuki syndrome. Of these, 12 had causative variants in the two known Kabuki syndrome genes. In 2, we identified presumptive loss of function de novo variants in KMT2A (missense and splice site variants), a gene that encodes another histone modifying enzyme previously exclusively associated with Wiedermann-Steiner syndrome. Although Kabuki syndrome is a disorder of histone modification, we also find alterations in DNA methylation among individuals with a Kabuki syndrome diagnosis relative to matched normal controls, regardless of whether they carry a variant in KMT2A or KMT2D or not. Furthermore, we observed characteristic global abnormalities of DNA methylation that distinguished patients with a loss of function variant in KMT2D or missense or splice site variants in either KMT2D or KMT2A from normal controls. Our results provide new insights into the relationship of genotype to epigenotype and phenotype and indicate cross-talk between histone and DNA methylation machineries exposed by inborn errors of the epigenetic apparatus.
Keywords: Abnormalities, Multiple; Case-Control Studies; Child; DNA Methylation; Face; Female; Hematologic Diseases; Histone-Lysine N-Methyltransferase; Humans; Loss of Function Mutation; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Vestibular Diseases

Phenotypic and molecular characterisation of CDK13-related congenital heart defects, dysmorphic facial features and intellectual developmental disorders. - Bostwick, Bret L; McLean, Scott; Posey, Jennifer E; Streff, Haley E; Gripp, Karen W; Blesson, Alyssa; Powell-Hamilton, Nina; Tusi, Jessica; Stevenson, David A; Farrelly, Ellyn; Hudgins, Louanne; Yang, Yaping; et al. (Genome Med, 2017)
BACKGROUND: De novo missense variants in CDK13 have been described as the cause of syndromic congenital heart defects in seven individuals ascertained from a large congenital cardiovascular malformations cohort. We aimed to further define the phenotypic and molecular spectrum of this newly described disorder. METHODS: To minimise ascertainment bias, we recruited nine additional individuals with CDK13 pathogenic variants from clinical and research exome laboratory sequencing cohorts. Each individual underwent dysmorphology exam and comprehensive medical history review. RESULTS: We demonstrate greater than expected phenotypic heterogeneity, including 33% (3/9) of individuals without structural heart disease on echocardiogram. There was a high penetrance for a unique constellation of facial dysmorphism and global developmental delay, as well as less frequently seen renal and sacral anomalies. Two individuals had novel CDK13 variants (p.Asn842Asp, p.Lys734Glu), while the remaining seven unrelated individuals had a recurrent, previously published p.Asn842Ser variant. Summary of all variants published to date demonstrates apparent restriction of pathogenic variants to the protein kinase domain with clustering in the ATP and magnesium binding sites. CONCLUSIONS: Here we provide detailed phenotypic and molecular characterisation of individuals with pathogenic variants in CDK13 and propose management guidelines based upon the estimated prevalence of anomalies identified.
Keywords: Adolescent; Adult; CDC2 Protein Kinase; Child; Child, Preschool; Face; Female; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Mutation; Phenotype; Syndrome

Phenotypic spectrum of autosomal recessive congenital ichthyosis due to PNPLA1 mutation. - Boyden, L M; Craiglow, B G; Hu, R H; Zhou, J; Browning, J; Eichenfield, L; Lim, Y L; Luu, M; Randolph, L M; Ginarte, M; Fachal, L; Rodriguez-Pazos, L; et al. (Br J Dermatol, 2017)
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Child; Child, Preschool; Female; Heterozygote; Homozygote; Humans; Ichthyosis; Infant; Lipase; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Young Adult

A postnatal role for embryonic myosin revealed by MYH3 mutations that alter TGFβ signaling and cause autosomal dominant spondylocarpotarsal synostosis. - Zieba, Jennifer; Zhang, Wenjuan; Chong, Jessica X; Forlenza, Kimberly N; Martin, Jorge H; Heard, Kelly; Grange, Dorothy K; Butler, Merlin G; Kleefstra, Tjitske; Lachman, Ralph S; Nickerson, Deborah; Regnier, Michael; et al. (Sci Rep, 2017)
Spondylocarpotarsal synostosis (SCT) is a skeletal disorder characterized by progressive vertebral, carpal and tarsal fusions, and mild short stature. The majority of affected individuals have an autosomal recessive form of SCT and are homozygous or compound heterozygous for nonsense mutations in the gene that encodes the cytoskeletal protein filamin B (FLNB), but a subset do not have FLNB mutations. Exome sequence analysis of three SCT patients negative for FLNB mutations identified an autosomal dominant form of the disease due to heterozygosity for missense or nonsense mutations in MYH3, which encodes embryonic myosin. Cells transfected with the MYH3 missense mutations had reduced TGFβ signaling, revealing a regulatory role for embryonic myosin in the TGFβ signaling pathway. In wild-type mice, there was persistent postnatal expression of embryonic myosin in the small muscles joining the neural arches of the spine suggesting that loss of myosin function in these muscles contribute to the disease. Our findings demonstrate that dominant mutations in MYH3 underlie autosomal dominant SCT, identify a postnatal role for embryonic myosin and suggest that altered regulation of signal transduction in the muscles within the spine may lead to the development of vertebral fusions.
Keywords: Abnormalities, Multiple; Alleles; Bone Morphogenetic Proteins; Cytoskeletal Proteins; Female; Genes, Dominant; Genotype; Humans; Lumbar Vertebrae; Male; Musculoskeletal Diseases; Mutation; Myosins; Phenotype; Radiography; Scoliosis; Signal Transduction; Synostosis; Thoracic Vertebrae; Transforming Growth Factor beta; Whole Exome Sequencing

Presynaptic congenital myasthenic syndrome with a homozygous sequence variant in LAMA5 combines myopia, facial tics, and failure of neuromuscular transmission. - Maselli, Ricardo A; Arredondo, Juan; Vázquez, Jessica; Chong, Jessica X; Bamshad, Michael J; Nickerson, Deborah A; Lara, Marian; Ng, Fiona; Lo, Victoria L; Pytel, Peter; McDonald, Craig M (Am J Med Genet A, 2017)
Defects in genes encoding the isoforms of the laminin alpha subunit have been linked to various phenotypic manifestations, including brain malformations, muscular dystrophy, ocular defects, cardiomyopathy, and skin abnormalities. We report here a severe defect of neuromuscular transmission in a consanguineous patient with a homozygous variant in the laminin alpha-5 subunit gene (LAMA5). The variant c.8046C>T (p.Arg2659Trp) is rare and has a predicted deleterious effect. The affected individual, who also carries a rare homozygous sequence variant in LAMA1, had muscle weakness, myopia, and facial tics. Magnetic resonance imaging of brain showed mild volume loss and periventricular T2 prolongation. Repetitive nerve stimulation revealed 50% decrement of compound muscle action potential amplitudes and 250% facilitation immediately after exercise, Endplate studies identified a profound reduction of the endplate potential quantal content and endplates with normal postsynaptic folding that were denuded or partially occupied by small nerve terminals. Expression studies revealed that p.Arg2659Trp caused decreased binding of laminin alpha-5 to SV2A and impaired laminin-521 cell-adhesion and cell projection support in primary neuronal cultures. In summary, this report describing severe neuromuscular transmission failure in a patient with a LAMA5 mutation expands the list of phenotypes associated with defects in genes encoding alpha-laminins.
Keywords: Adult; Face; Female; Homozygote; Humans; Laminin; Myasthenic Syndromes, Congenital; Myopia; Neuromuscular Junction Diseases; Tics; Young Adult

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Yuan, Bo; Jhangiani, Shalini N; Muzny, Donna M; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult

PRUNE is crucial for normal brain development and mutated in microcephaly with neurodevelopmental impairment. - Zollo, Massimo; Ahmed, Mustafa; Ferrucci, Veronica; Salpietro, Vincenzo; Asadzadeh, Fatemeh; Carotenuto, Marianeve; Maroofian, Reza; Al-Amri, Ahmed; Singh, Royana; Scognamiglio, Iolanda; Mojarrad, Majid; Musella, Luca; et al. (Brain, 2017)
PRUNE is a member of the DHH (Asp-His-His) phosphoesterase protein superfamily of molecules important for cell motility, and implicated in cancer progression. Here we investigated multiple families from Oman, India, Iran and Italy with individuals affected by a new autosomal recessive neurodevelopmental and degenerative disorder in which the cardinal features include primary microcephaly and profound global developmental delay. Our genetic studies identified biallelic mutations of PRUNE1 as responsible. Our functional assays of disease-associated variant alleles revealed impaired microtubule polymerization, as well as cell migration and proliferation properties, of mutant PRUNE. Additionally, our studies also highlight a potential new role for PRUNE during microtubule polymerization, which is essential for the cytoskeletal rearrangements that occur during cellular division and proliferation. Together these studies define PRUNE as a molecule fundamental for normal human cortical development and define cellular and clinical consequences associated with PRUNE mutation.
Keywords: Adolescent; Brain; Carrier Proteins; Cell Differentiation; Cell Movement; Cerebral Cortex; Child; Child, Preschool; Cytoskeleton; Developmental Disabilities; Female; Genes, Recessive; Heredodegenerative Disorders, Nervous System; Humans; Infant; Male; Microcephaly; Microtubules; Mutation; Pedigree; Young Adult

Pyruvate dehydrogenase complex-E2 deficiency causes paroxysmal exercise-induced dyskinesia. - Friedman, Jennifer; Feigenbaum, Annette; Chuang, Nathaniel; Silhavy, Jennifer; Gleeson, Joseph G (Neurology, 2017)

Rare Genetic Variants in PARN Are Associated with Pulmonary Fibrosis in Families. - Kropski, Jonathan A; Reiss, Sara; Markin, Cheryl; Brown, Kevin K; Schwartz, David A; Schwarz, Marvin I; Loyd, James E; Phillips, John A; Blackwell, Timothy S; Cogan, Joy D (Am J Respir Crit Care Med, 2017)
Keywords: Genetic Variation; Humans; Pulmonary Fibrosis

A Recurrent De Novo Variant in NACC1 Causes a Syndrome Characterized by Infantile Epilepsy, Cataracts, and Profound Developmental Delay. - Schoch, Kelly; Meng, Linyan; Szelinger, Szabolcs; Bearden, David R; Stray-Pedersen, Asbjorg; Busk, Oyvind L; Stong, Nicholas; Liston, Eriskay; Cohn, Ronald D; Scaglia, Fernando; Rosenfeld, Jill A; Tarpinian, Jennifer; et al. (Am J Hum Genet, 2017)
Whole-exome sequencing (WES) has increasingly enabled new pathogenic gene variant identification for undiagnosed neurodevelopmental disorders and provided insights into both gene function and disease biology. Here, we describe seven children with a neurodevelopmental disorder characterized by microcephaly, profound developmental delays and/or intellectual disability, cataracts, severe epilepsy including infantile spasms, irritability, failure to thrive, and stereotypic hand movements. Brain imaging in these individuals reveals delay in myelination and cerebral atrophy. We observe an identical recurrent de novo heterozygous c.892C>T (p.Arg298Trp) variant in the nucleus accumbens associated 1 (NACC1) gene in seven affected individuals. One of the seven individuals is mosaic for this variant. NACC1 encodes a transcriptional repressor implicated in gene expression and has not previously been associated with germline disorders. The probability of finding the same missense NACC1 variant by chance in 7 out of 17,228 individuals who underwent WES for diagnoses of neurodevelopmental phenotypes is extremely small and achieves genome-wide significance (p = 1.25 × 10). Selective constraint against missense variants in NACC1 makes this excess of an identical missense variant in all seven individuals more remarkable. Our findings are consistent with a germline recurrent mutational hotspot associated with an allele-specific neurodevelopmental phenotype in NACC1.
Keywords: Alleles; Amino Acid Sequence; Brain; Cataract; Child; Child, Preschool; Female; Genetic Variation; Genome-Wide Association Study; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Microcephaly; Mutation, Missense; Neoplasm Proteins; Pedigree; Phenotype; Repressor Proteins; Spasms, Infantile

Resolution of Disease Phenotypes Resulting from Multilocus Genomic Variation. - Posey, Jennifer E; Harel, Tamar; Liu, Pengfei; Rosenfeld, Jill A; James, Regis A; Coban Akdemir, Zeynep H; Walkiewicz, Magdalena; Bi, Weimin; Xiao, Rui; Ding, Yan; Xia, Fan; Beaudet, Arthur L; et al. (N Engl J Med, 2017)
BACKGROUND: Whole-exome sequencing can provide insight into the relationship between observed clinical phenotypes and underlying genotypes. METHODS: We conducted a retrospective analysis of data from a series of 7374 consecutive unrelated patients who had been referred to a clinical diagnostic laboratory for whole-exome sequencing; our goal was to determine the frequency and clinical characteristics of patients for whom more than one molecular diagnosis was reported. The phenotypic similarity between molecularly diagnosed pairs of diseases was calculated with the use of terms from the Human Phenotype Ontology. RESULTS: A molecular diagnosis was rendered for 2076 of 7374 patients (28.2%); among these patients, 101 (4.9%) had diagnoses that involved two or more disease loci. We also analyzed parental samples, when available, and found that de novo variants accounted for 67.8% (61 of 90) of pathogenic variants in autosomal dominant disease genes and 51.7% (15 of 29) of pathogenic variants in X-linked disease genes; both variants were de novo in 44.7% (17 of 38) of patients with two monoallelic variants. Causal copy-number variants were found in 12 patients (11.9%) with multiple diagnoses. Phenotypic similarity scores were significantly lower among patients in whom the phenotype resulted from two distinct mendelian disorders that affected different organ systems (50 patients) than among patients with disorders that had overlapping phenotypic features (30 patients) (median score, 0.21 vs. 0.36; P=1.77×10). CONCLUSIONS: In our study, we found multiple molecular diagnoses in 4.9% of cases in which whole-exome sequencing was informative. Our results show that structured clinical ontologies can be used to determine the degree of overlap between two mendelian diseases in the same patient; the diseases can be distinct or overlapping. Distinct disease phenotypes affect different organ systems, whereas overlapping disease phenotypes are more likely to be caused by two genes encoding proteins that interact within the same pathway. (Funded by the National Institutes of Health and the Ting Tsung and Wei Fong Chao Foundation.).
Keywords: Exome; Genetic Diseases, Inborn; Genetic Variation; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Phenotype; Retrospective Studies; Sequence Analysis, DNA

REST Final-Exon-Truncating Mutations Cause Hereditary Gingival Fibromatosis. - Bayram, Yavuz; White, Janson J; Elcioglu, Nursel; Cho, Megan T; Zadeh, Neda; Gedikbasi, Asuman; Palanduz, Sukru; Ozturk, Sukru; Cefle, Kivanc; Kasapcopur, Ozgur; Coban Akdemir, Zeynep; Pehlivan, Davut; et al. (Am J Hum Genet, 2017)
Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis that develops as a slowly progressive, benign, localized or generalized enlargement of keratinized gingiva. HGF is a genetically heterogeneous disorder and can be transmitted either as an autosomal-dominant or autosomal-recessive trait or appear sporadically. To date, four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15) have been mapped to autosomes and one gene (SOS1) has been associated with the HGF trait observed to segregate in a dominant inheritance pattern. Here we report 11 individuals with HGF from three unrelated families. Whole-exome sequencing (WES) revealed three different truncating mutations including two frameshifts and one nonsense variant in RE1-silencing transcription factor (REST) in the probands from all families and further genetic and genomic analyses confirmed the WES-identified findings. REST is a transcriptional repressor that is expressed throughout the body; it has different roles in different cellular contexts, such as oncogenic and tumor-suppressor functions and hematopoietic and cardiac differentiation. Here we show the consequences of germline final-exon-truncating mutations in REST for organismal development and the association with the HGF phenotype.
Keywords: Adolescent; Base Sequence; Chromosome Segregation; Exons; Family; Female; Fibromatosis, Gingival; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Repressor Proteins

The sensitivity of exome sequencing in identifying pathogenic mutations for LGMD in the United States. - Reddy, Hemakumar M; Cho, Kyung-Ah; Lek, Monkol; Estrella, Elicia; Valkanas, Elise; Jones, Michael D; Mitsuhashi, Satomi; Darras, Basil T; Amato, Anthony A; Lidov, Hart Gw; Brownstein, Catherine A; Margulies, David M; et al. (J Hum Genet, 2017)
The current study characterizes a cohort of limb-girdle muscular dystrophy (LGMD) in the United States using whole-exome sequencing. Fifty-five families affected by LGMD were recruited using an institutionally approved protocol. Exome sequencing was performed on probands and selected parental samples. Pathogenic mutations and cosegregation patterns were confirmed by Sanger sequencing. Twenty-two families (40%) had novel and previously reported pathogenic mutations, primarily in LGMD genes, and also in genes for Duchenne muscular dystrophy, facioscapulohumeral muscular dystrophy, congenital myopathy, myofibrillar myopathy, inclusion body myopathy and Pompe disease. One family was diagnosed via clinical testing. Dominant mutations were identified in COL6A1, COL6A3, FLNC, LMNA, RYR1, SMCHD1 and VCP, recessive mutations in ANO5, CAPN3, GAA, LAMA2, SGCA and SGCG, and X-linked mutations in DMD. A previously reported variant in DMD was confirmed to be benign. Exome sequencing is a powerful diagnostic tool for LGMD. Despite careful phenotypic screening, pathogenic mutations were found in other muscle disease genes, largely accounting for the increased sensitivity of exome sequencing. Our experience suggests that broad sequencing panels are useful for these analyses because of the phenotypic overlap of many neuromuscular conditions. The confirmation of a benign DMD variant illustrates the potential of exome sequencing to help determine pathogenicity.
Keywords: Base Sequence; Distal Myopathies; Exome; Female; Genetic Testing; Glycogen Storage Disease Type II; Humans; Male; Muscular Dystrophies, Limb-Girdle; Muscular Dystrophy, Duchenne; Muscular Dystrophy, Facioscapulohumeral; Mutation; Myopathies, Structural, Congenital; Sequence Analysis, DNA; United States

Sequence variants in nine different genes underlying rare skin disorders in 10 consanguineous families. - Shah, Khadim; Mehmood, Sabba; Jan, Abid; Abbe, Izoduwa; Hussain Ali, Raja; Khan, Anwar; Chishti, Muhammad S; Lee, Kwanghyuk; Ahmad, Farooq; Ansar, Muhammad; Shahzad, Shaheen; Nickerson, Deborah A; et al. (Int J Dermatol, 2017)
BACKGROUND: Genodermatoses represent genetic anomalies of skin tissues including hair follicles, sebaceous glands, eccrine glands, nails, and teeth. Ten consanguineous families segregating various genodermatosis phenotypes were investigated in the present study. METHODS: Homozygosity mapping, exome, and Sanger sequencing were employed to search for the disease-causing variants in the 10 families. RESULTS: Exome sequencing identified seven homozygous sequence variants in different families, including: c.27delT in FERMT1; c.836delA in ABHD5; c.2453C>T in ERCC5; c.5314C>T in COL7A1; c.1630C>T in ALOXE3; c.502C>T in PPOX; and c.10G>T in ALDH3A2. Sanger sequencing revealed three homozygous variants: c.1718 + 2A>G in FERMT1; c.10459A>T in FLG; and c.92delT in the KRT14 genes as the underlying genetic cause of skin phenotypes. CONCLUSION: This study supports the use of exome sequencing as a powerful, efficient tool for identifying genes that underlie rare monogenic skin disorders.
Keywords: 1-Acylglycerol-3-Phosphate O-Acyltransferase; Aldehyde Oxidoreductases; Blister; Collagen Type VII; Consanguinity; DNA Mutational Analysis; DNA-Binding Proteins; Endonucleases; Epidermolysis Bullosa; Epidermolysis Bullosa Dystrophica; Epidermolysis Bullosa Simplex; Exome; Female; Flavoproteins; Homozygote; Humans; Ichthyosiform Erythroderma, Congenital; Ichthyosis Vulgaris; Ichthyosis, Lamellar; INDEL Mutation; Intermediate Filament Proteins; Keratin-14; Lipid Metabolism, Inborn Errors; Lipoxygenase; Male; Membrane Proteins; Mitochondrial Proteins; Muscular Diseases; Neoplasm Proteins; Nuclear Proteins; Pedigree; Periodontal Diseases; Phenotype; Photosensitivity Disorders; Porphyria, Variegate; Protoporphyrinogen Oxidase; Rare Diseases; Sjogren-Larsson Syndrome; Skin Diseases, Genetic; Transcription Factors; Xeroderma Pigmentosum

Sequencing of sporadic Attention-Deficit Hyperactivity Disorder (ADHD) identifies novel and potentially pathogenic de novo variants and excludes overlap with genes associated with autism spectrum disorder. - Kim, Daniel Seung; Burt, Amber A; Ranchalis, Jane E; Wilmot, Beth; Smith, Joshua D; Patterson, Karynne E; Coe, Bradley P; Li, Yatong K; Bamshad, Michael J; Nikolas, Molly; Eichler, Evan E; Swanson, James M; et al. (Am J Med Genet B Neuropsychiatr Genet, 2017)
Attention-Deficit Hyperactivity Disorder (ADHD) has high heritability; however, studies of common variation account for <5% of ADHD variance. Using data from affected participants without a family history of ADHD, we sought to identify de novo variants that could account for sporadic ADHD. Considering a total of 128 families, two analyses were conducted in parallel: first, in 11 unaffected parent/affected proband trios (or quads with the addition of an unaffected sibling) we completed exome sequencing. Six de novo missense variants at highly conserved bases were identified and validated from four of the 11 families: the brain-expressed genes TBC1D9, DAGLA, QARS, CSMD2, TRPM2, and WDR83. Separately, in 117 unrelated probands with sporadic ADHD, we sequenced a panel of 26 genes implicated in intellectual disability (ID) and autism spectrum disorder (ASD) to evaluate whether variation in ASD/ID-associated genes were also present in participants with ADHD. Only one putative deleterious variant (Gln600STOP) in CHD1L was identified; this was found in a single proband. Notably, no other nonsense, splice, frameshift, or highly conserved missense variants in the 26 gene panel were identified and validated. These data suggest that de novo variant analysis in families with independently adjudicated sporadic ADHD diagnosis can identify novel genes implicated in ADHD pathogenesis. Moreover, that only one of the 128 cases (0.8%, 11 exome, and 117 MIP sequenced participants) had putative deleterious variants within our data in 26 genes related to ID and ASD suggests significant independence in the genetic pathogenesis of ADHD as compared to ASD and ID phenotypes. © 2017 Wiley Periodicals, Inc.
Keywords: Adult; Attention Deficit Disorder with Hyperactivity; Autism Spectrum Disorder; Biomarkers; Child; Exome; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation, Missense; Phenotype

SLC13A5 is the second gene associated with Kohlschütter-Tönz syndrome. - Schossig, Anna; Bloch-Zupan, Agnès; Lussi, Adrian; Wolf, Nicole I; Raskin, Salmo; Cohen, Monika; Giuliano, Fabienne; Jurgens, Julie; Krabichler, Birgit; Koolen, David A; de Macena Sobreira, Nara Lygia; Maurer, Elisabeth; et al. (J Med Genet, 2017)
BACKGROUND: Kohlschütter-Tönz syndrome (KTZS) is a rare autosomal-recessive disease characterised by epileptic encephalopathy, intellectual disability and amelogenesis imperfecta (AI). It is frequently caused by biallelic mutations in ROGDI. Here, we report on individuals with ROGDI-negative KTZS carrying biallelic SLC13A5 mutations. METHODS: In the present cohort study, nine individuals from four families with the clinical diagnosis of KTZS and absence of ROGDI mutations as well as one patient with unexplained epileptic encephalopathy were investigated by clinical and dental evaluation, parametric linkage analysis (one family), and exome and/or Sanger sequencing. Dental histological investigations were performed on teeth from individuals with SLC13A5-associated and ROGDI-associated KTZS. RESULTS: Biallelic mutations in SLC13A5 were identified in 10 affected individuals. Epileptic encephalopathy usually presents in the neonatal and (less frequently) early infantile period. Yellowish to orange discolouration of both deciduous and permanent teeth, as well as wide interdental spaces and abnormal crown forms are major clinical signs of individuals with biallelic SLC13A5 mutations. Histological dental investigations confirmed the clinical diagnosis of hypoplastic AI. In comparison, the histological evaluation of a molar assessed from an individual with ROGDI-associated KTZS revealed hypocalcified AI. CONCLUSIONS: We conclude that SLC13A5 is the second major gene associated with the clinical diagnosis of KTZS, characterised by neonatal epileptic encephalopathy and hypoplastic AI. Careful clinical and dental delineation provides clues whether ROGDI or SLC13A5 is the causative gene. Hypersensitivity of teeth as well as high caries risk requires individual dental prophylaxis and attentive dental management.
Keywords: Alleles; Amelogenesis Imperfecta; Brain Diseases; Cohort Studies; Dementia; Epilepsy; Exome; Female; Genetic Linkage; Genetic Predisposition to Disease; Humans; Male; Membrane Proteins; Mutation; Nuclear Proteins; Pedigree; Symporters; Tooth

SMCHD1 mutations associated with a rare muscular dystrophy can also cause isolated arhinia and Bosma arhinia microphthalmia syndrome. - Shaw, Natalie D; Brand, Harrison; Kupchinsky, Zachary A; Bengani, Hemant; Plummer, Lacey; Jones, Takako I; Erdin, Serkan; Williamson, Kathleen A; Rainger, Joe; Stortchevoi, Alexei; Samocha, Kaitlin; Currall, Benjamin B; et al. (Nat Genet, 2017)
Arhinia, or absence of the nose, is a rare malformation of unknown etiology that is often accompanied by ocular and reproductive defects. Sequencing of 40 people with arhinia revealed that 84% of probands harbor a missense mutation localized to a constrained region of SMCHD1 encompassing the ATPase domain. SMCHD1 mutations cause facioscapulohumeral muscular dystrophy type 2 (FSHD2) via a trans-acting loss-of-function epigenetic mechanism. We discovered shared mutations and comparable DNA hypomethylation patterning between these distinct disorders. CRISPR/Cas9-mediated alteration of smchd1 in zebrafish yielded arhinia-relevant phenotypes. Transcriptome and protein analyses in arhinia probands and controls showed no differences in SMCHD1 mRNA or protein abundance but revealed regulatory changes in genes and pathways associated with craniofacial patterning. Mutations in SMCHD1 thus contribute to distinct phenotypic spectra, from craniofacial malformation and reproductive disorders to muscular dystrophy, which we speculate to be consistent with oligogenic mechanisms resulting in pleiotropic outcomes.
Keywords: Adolescent; Child; Child, Preschool; Choanal Atresia; Chromosomal Proteins, Non-Histone; Female; Genetic Predisposition to Disease; Humans; Infant; Male; Microphthalmos; Muscular Dystrophies; Mutation; Nose; Phenotype

Survival beyond the perinatal period expands the phenotypes caused by mutations in GLE1. - Said, Edith; Chong, Jessica X; Hempel, Maja; Denecke, Jonas; Soler, Paul; Strom, Tim; Nickerson, Deborah A; Kubisch, Christian; Bamshad, Michael J; Lessel, Davor (Am J Med Genet A, 2017)
Mutations in GLE1 underlie Lethal Congenital Contracture syndrome (LCCS) and Lethal Arthrogryposis with Anterior Horn Cell Disease (LAAHD). Both LCCS and LAAHD are characterized by reduced fetal movements, congenital contractures, and a severe form of motor neuron disease that results in fetal death or death in the perinatal period, respectively. We identified bi-allelic mutations in GLE1 in two unrelated individuals with motor delays, feeding difficulties, and respiratory insufficiency who survived beyond the perinatal period. Each affected child had missense variants predicted to result in amino acid substitutions near the C-terminus of GLE1 that are predicted to disrupt protein-protein interaction or GLE1 protein targeting. We hypothesize that mutations that preserve function of the coiled-coil domain of GLE1 cause LAAHD whereas mutations that abolish the function of the coiled-coil domain cause LCCS. The phenotype of LAAHD is now expanded to include multiple individuals surviving into childhood suggesting that LAAHD is a misnomer and should be re-named Arthrogryposis with Anterior Horn Cell Disease (AAHD).
Keywords: Arthrogryposis; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Male; Motor Disorders; Motor Neuron Disease; Mutation; Nucleocytoplasmic Transport Proteins; Pedigree; Pregnancy

SVachra: a tool to identify genomic structural variation in mate pair sequencing data containing inward and outward facing reads. - Hampton, Oliver A; English, Adam C; Wang, Mark; Salerno, William J; Liu, Yue; Muzny, Donna M; Han, Yi; Wheeler, David A; Worley, Kim C; Lupski, James R; Gibbs, Richard A (BMC Genomics, 2017)
BACKGROUND: Characterization of genomic structural variation (SV) is essential to expanding the research and clinical applications of genome sequencing. Reliance upon short DNA fragment paired end sequencing has yielded a wealth of single nucleotide variants and internal sequencing read insertions-deletions, at the cost of limited SV detection. Multi-kilobase DNA fragment mate pair sequencing has supplemented the void in SV detection, but introduced new analytic challenges requiring SV detection tools specifically designed for mate pair sequencing data. Here, we introduce SVachra - Structural Variation Assessment of CHRomosomal Aberrations, a breakpoint calling program that identifies large insertions-deletions, inversions, inter- and intra-chromosomal translocations utilizing both inward and outward facing read types generated by mate pair sequencing. RESULTS: We demonstrate SVachra's utility by executing the program on large-insert (Illumina Nextera) mate pair sequencing data from the personal genome of a single subject (HS1011). An additional data set of long-read (Pacific BioSciences RSII) was also generated to validate SV calls from SVachra and other comparison SV calling programs. SVachra exhibited the highest validation rate and reported the widest distribution of SV types and size ranges when compared to other SV callers. CONCLUSIONS: SVachra is a highly specific breakpoint calling program that exhibits a more unbiased SV detection methodology than other callers.
Keywords: Genetic Variation; Genomics; Sequence Analysis, DNA

Unraveling genetic predisposition to familial or early onset gastric cancer using germline whole-exome sequencing. - Vogelaar, Ingrid P; van der Post, Rachel S; van Krieken, J Han Jm; Spruijt, Liesbeth; van Zelst-Stams, Wendy Ag; Kets, C Marleen; Lubinski, Jan; Jakubowska, Anna; Teodorczyk, Urszula; Aalfs, Cora M; van Hest, Liselotte P; Pinheiro, Hugo; et al. (Eur J Hum Genet, 2017)
Recognition of individuals with a genetic predisposition to gastric cancer (GC) enables preventive measures. However, the underlying cause of genetic susceptibility to gastric cancer remains largely unexplained. We performed germline whole-exome sequencing on leukocyte DNA of 54 patients from 53 families with genetically unexplained diffuse-type and intestinal-type GC to identify novel GC-predisposing candidate genes. As young age at diagnosis and familial clustering are hallmarks of genetic tumor susceptibility, we selected patients that were diagnosed below the age of 35, patients from families with two cases of GC at or below age 60 and patients from families with three GC cases at or below age 70. All included individuals were tested negative for germline CDH1 mutations before or during the study. Variants that were possibly deleterious according to in silico predictions were filtered using several independent approaches that were based on gene function and gene mutation burden in controls. Despite a rigorous search, no obvious candidate GC predisposition genes were identified. This negative result stresses the importance of future research studies in large, homogeneous cohorts.
Keywords: Adult; Aged; Antigens, CD; Cadherins; Early Detection of Cancer; Exome; Female; Genetic Predisposition to Disease; Genetic Testing; Germ-Line Mutation; Humans; Male; Middle Aged; Sequence Analysis, DNA; Stomach Neoplasms

Use of Exome Sequencing for Infants in Intensive Care Units: Ascertainment of Severe Single-Gene Disorders and Effect on Medical Management. - Meng, Linyan; Pammi, Mohan; Saronwala, Anirudh; Magoulas, Pilar; Ghazi, Andrew Ray; Vetrini, Francesco; Zhang, Jing; He, Weimin; Dharmadhikari, Avinash V; Qu, Chunjing; Ward, Patricia; Braxton, Alicia; et al. (JAMA Pediatr, 2017)
Importance: While congenital malformations and genetic diseases are a leading cause of early infant death, to our knowledge, the contribution of single-gene disorders in this group is undetermined. Objective: To determine the diagnostic yield and use of clinical exome sequencing in critically ill infants. Design, Setting, and Participants: Clinical exome sequencing was performed for 278 unrelated infants within the first 100 days of life who were admitted to Texas Children's Hospital in Houston, Texas, during a 5-year period between December 2011 and January 2017. Exome sequencing types included proband exome, trio exome, and critical trio exome, a rapid genomic assay for seriously ill infants. Main Outcomes and Measures: Indications for testing, diagnostic yield of clinical exome sequencing, turnaround time, molecular findings, patient age at diagnosis, and effect on medical management among a group of critically ill infants who were suspected to have genetic disorders. Results: The mean (SEM) age for infants participating in the study was 28.5 (1.7) days; of these, the mean (SEM) age was 29.0 (2.2) days for infants undergoing proband exome sequencing, 31.5 (3.9) days for trio exome, and 22.7 (3.9) days for critical trio exome. Clinical indications for exome sequencing included a range of medical concerns. Overall, a molecular diagnosis was achieved in 102 infants (36.7%) by clinical exome sequencing, with relatively low yield for cardiovascular abnormalities. The diagnosis affected medical management for 53 infants (52.0%) and had a substantial effect on informed redirection of care, initiation of new subspecialist care, medication/dietary modifications, and furthering life-saving procedures in select patients. Critical trio exome sequencing revealed a molecular diagnosis in 32 of 63 infants (50.8%) at a mean (SEM) of 33.1 (5.6) days of life with a mean (SEM) turnaround time of 13.0 (0.4) days. Clinical care was altered by the diagnosis in 23 of 32 patients (71.9%). The diagnostic yield, patient age at diagnosis, and medical effect in the group that underwent critical trio exome sequencing were significantly different compared with the group who underwent regular exome testing. For deceased infants (n = 81), genetic disorders were molecularly diagnosed in 39 (48.1%) by exome sequencing, with implications for recurrence risk counseling. Conclusions and Relevance: Exome sequencing is a powerful tool for the diagnostic evaluation of critically ill infants with suspected monogenic disorders in the neonatal and pediatric intensive care units and its use has a notable effect on clinical decision making.
Keywords: Adult; Critical Care; Disease Management; Exome; Genetic Counseling; Genetic Diseases, Inborn; Humans; Infant; Infant Care; Infant, Newborn; Intensive Care Units, Pediatric; Length of Stay; Retrospective Studies; Texas; Whole Exome Sequencing

Whole exome sequencing in 342 congenital cardiac left sided lesion cases reveals extensive genetic heterogeneity and complex inheritance patterns. - Li, Alexander H; Hanchard, Neil A; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid; Nicosia, Annarita; Rosenfeld, Jill; Muzny, Donna; D'Alessandro, Lisa C A; Morris, Shaine; Jhangiani, Shalini; Parekh, Dhaval R; et al. (Genome Med, 2017)
BACKGROUND: Left-sided lesions (LSLs) account for an important fraction of severe congenital cardiovascular malformations (CVMs). The genetic contributions to LSLs are complex, and the mutations that cause these malformations span several diverse biological signaling pathways: TGFB, NOTCH, SHH, and more. Here, we use whole exome sequence data generated in 342 LSL cases to identify likely damaging variants in putative candidate CVM genes. METHODS: Using a series of bioinformatics filters, we focused on genes harboring population-rare, putative loss-of-function (LOF), and predicted damaging variants in 1760 CVM candidate genes constructed a priori from the literature and model organism databases. Gene variants that were not observed in a comparably sequenced control dataset of 5492 samples without severe CVM were then subjected to targeted validation in cases and parents. Whole exome sequencing data from 4593 individuals referred for clinical sequencing were used to bolster evidence for the role of candidate genes in CVMs and LSLs. RESULTS: Our analyses revealed 28 candidate variants in 27 genes, including 17 genes not previously associated with a human CVM disorder, and revealed diverse patterns of inheritance among LOF carriers, including 9 confirmed de novo variants in both novel and newly described human CVM candidate genes (ACVR1, JARID2, NR2F2, PLRG1, SMURF1) as well as established syndromic CVM genes (KMT2D, NF1, TBX20, ZEB2). We also identified two genes (DNAH5, OFD1) with evidence of recessive and hemizygous inheritance patterns, respectively. Within our clinical cohort, we also observed heterozygous LOF variants in JARID2 and SMAD1 in individuals with cardiac phenotypes, and collectively, carriers of LOF variants in our candidate genes had a four times higher odds of having CVM (odds ratio = 4.0, 95% confidence interval 2.5-6.5). CONCLUSIONS: Our analytical strategy highlights the utility of bioinformatic resources, including human disease records and model organism phenotyping, in novel gene discovery for rare human disease. The results underscore the extensive genetic heterogeneity underlying non-syndromic LSLs, and posit potential novel candidate genes and complex modes of inheritance in this important group of birth defects.
Keywords: Female; Genetic Heterogeneity; Heart Defects, Congenital; Humans; Inheritance Patterns; Male; Whole Exome Sequencing

Whole-exome sequencing in the molecular diagnosis of individuals with congenital anomalies of the kidney and urinary tract and identification of a new causative gene. - Bekheirnia, Mir Reza; Bekheirnia, Nasim; Bainbridge, Matthew N; Gu, Shen; Coban Akdemir, Zeynep Hande; Gambin, Tomek; Janzen, Nicolette K; Jhangiani, Shalini N; Muzny, Donna M; Michael, Mini; Brewer, Eileen D; Elenberg, Ewa; et al. (Genet Med, 2017)
PURPOSE: To investigate the utility of whole-exome sequencing (WES) to define a molecular diagnosis for patients clinically diagnosed with congenital anomalies of kidney and urinary tract (CAKUT). METHODS: WES was performed in 62 families with CAKUT. WES data were analyzed for single-nucleotide variants (SNVs) in 35 known CAKUT genes, putatively deleterious sequence changes in new candidate genes, and potentially disease-associated copy-number variants (CNVs). RESULTS: In approximately 5% of families, pathogenic SNVs were identified in PAX2, HNF1B, and EYA1. Observed phenotypes in these families expand the current understanding about the role of these genes in CAKUT. Four pathogenic CNVs were also identified using two CNV detection tools. In addition, we found one deleterious de novo SNV in FOXP1 among the 62 families with CAKUT. The clinical database of the Baylor Miraca Genetics laboratory was queried and seven additional unrelated individuals with novel de novo SNVs in FOXP1 were identified. Six of these eight individuals with FOXP1 SNVs have syndromic urinary tract defects, implicating this gene in urinary tract development. CONCLUSION: We conclude that WES can be used to identify molecular etiology (SNVs, CNVs) in a subset of individuals with CAKUT. WES can also help identify novel CAKUT genes.Genet Med 19 4, 412-420.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Genetic Predisposition to Disease; Hepatocyte Nuclear Factor 1-beta; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Nuclear Proteins; PAX2 Transcription Factor; Pedigree; Polymorphism, Single Nucleotide; Protein Tyrosine Phosphatases; Repressor Proteins; Urogenital Abnormalities; Vesico-Ureteral Reflux; Young Adult

Whole-Exome Sequencing Reveals Mutations in a Clinically Unrecognizable Patient with Syndromic CAKUT: A Case Report. - van der Ven, Amelie T; Shril, Shirlee; Ityel, Hadas; Vivante, Asaf; Chen, Jing; Hwang, Daw-Yang; Laricchia, Kristen M; Lek, Monkol; Tasic, Velibor; Hildebrandt, Friedhelm (Mol Syndromol, 2017)
We present the case of a patient of Macedonian origin with unilateral renal agenesis and ureterovesical junction obstruction in combination with further abnormalities including midface hypoplasia, scoliosis as well as camptodactyly of one toe. Whole-exome sequencing analysis revealed compound heterozygous variants in the gene. Recessive variants in are a known cause of van Maldergem syndrome (VMS) in which congenital anomalies of the kidney and urinary tract are a less characteristic but common feature. The initial presentation of our patient was not clinically recognizable. However, in view of the molecular findings, the most likely diagnosis is a mild manifestation of VMS. Only very few publications have reported patients with VMS and mutations in to date. With this case, we hope to provide further insight into the phenotypic variability of this syndrome.

Whole-Genome Sequencing of Cytogenetically Balanced Chromosome Translocations Identifies Potentially Pathological Gene Disruptions and Highlights the Importance of Microhomology in the Mechanism of Formation. - Nilsson, Daniel; Pettersson, Maria; Gustavsson, Peter; Förster, Alisa; Hofmeister, Wolfgang; Wincent, Josephine; Zachariadis, Vasilios; Anderlid, Britt-Marie; Nordgren, Ann; Mäkitie, Outi; Wirta, Valtteri; Käller, Max; et al. (Hum Mutat, 2017)
Most balanced translocations are thought to result mechanistically from nonhomologous end joining or, in rare cases of recurrent events, by nonallelic homologous recombination. Here, we use low-coverage mate pair whole-genome sequencing to fine map rearrangement breakpoint junctions in both phenotypically normal and affected translocation carriers. In total, 46 junctions from 22 carriers of balanced translocations were characterized. Genes were disrupted in 48% of the breakpoints; recessive genes in four normal carriers and known dominant intellectual disability genes in three affected carriers. Finally, seven candidate disease genes were disrupted in five carriers with neurocognitive disabilities (SVOPL, SUSD1, TOX, NCALD, SLC4A10) and one XX-male carrier with Tourette syndrome (LYPD6, GPC5). Breakpoint junction analyses revealed microhomology and small templated insertions in a substantive fraction of the analyzed translocations (17.4%; n = 4); an observation that was substantiated by reanalysis of 37 previously published translocation junctions. Microhomology associated with templated insertions is a characteristic seen in the breakpoint junctions of rearrangements mediated by error-prone replication-based repair mechanisms. Our data implicate that a mechanism involving template switching might contribute to the formation of at least 15% of the interchromosomal translocation events.
Keywords: Base Sequence; Chromosome Breakage; Chromosome Mapping; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Genetic Association Studies; Genomics; Genotype; Homologous Recombination; Humans; In Situ Hybridization, Fluorescence; Karyotype; Male; Phenotype; Translocation, Genetic; Whole Genome Sequencing

ACOX2 deficiency: A disorder of bile acid synthesis with transaminase elevation, liver fibrosis, ataxia, and cognitive impairment. - Vilarinho, Sílvia; Sari, Sinan; Mazzacuva, Francesca; Bilguvar, Kaya; Esendagli-Yilmaz, Güldal; Jain, Dhanpat; Akyol, Gülen; Dalgiç, Buket; Günel, Murat; Clayton, Peter T; Lifton, Richard P (Proc Natl Acad Sci U S A, 2016)
Acyl CoA Oxidase 2 (ACOX2) encodes branched-chain acyl-CoA oxidase, a peroxisomal enzyme believed to be involved in the metabolism of branched-chain fatty acids and bile acid intermediates. Deficiency of this enzyme has not been described previously. We report an 8-y-old male with intermittently elevated transaminase levels, liver fibrosis, mild ataxia, and cognitive impairment. Exome sequencing revealed a previously unidentified homozygous premature termination mutation (p.Y69*) in ACOX2 Immunohistochemistry confirmed the absence of ACOX2 expression in the patient's liver, and biochemical analysis showed marked elevation of intermediate bile acids upstream of ACOX2. These findings define a potentially treatable inborn error of bile acid biosynthesis caused by ACOX2 deficiency.
Keywords: Ataxia; Bile Acids and Salts; Child; Cognitive Dysfunction; Homozygote; Humans; Infant; Infant, Newborn; Liver; Liver Cirrhosis; Loss of Function Mutation; Male; Mutation; Oxidation-Reduction; Oxidoreductases; Transaminases

Aggressive tumor growth and clinical evolution in a patient with X-linked acro-gigantism syndrome. - Naves, Luciana A; Daly, Adrian F; Dias, Luiz Augusto; Yuan, Bo; Zakir, Juliano Coelho Oliveira; Barra, Gustavo Barcellos; Palmeira, Leonor; Villa, Chiara; Trivellin, Giampaolo; Júnior, Armindo Jreige; Neto, Florêncio Figueiredo Cavalcante; Liu, Pengfei; et al. (Endocrine, 2016)
X-linked acro-gigantism (X-LAG) syndrome is a newly described disease caused by microduplications on chromosome Xq26.3 leading to copy number gain of GPR101. We describe the clinical progress of a sporadic male X-LAG syndrome patient with an Xq26.3 microduplication, highlighting the aggressive natural history of pituitary tumor growth in the absence of treatment. The patient first presented elsewhere aged 5 years 8 months with a history of excessive growth for >2 years. His height was 163 cm, his weight was 36 kg, and he had markedly elevated GH and IGF-1. MRI showed a non-invasive sellar mass measuring 32.5 × 23.9 × 29.1 mm. Treatment was declined and the family was lost to follow-up. At the age of 10 years and 7 months, he presented again with headaches, seizures, and visual disturbance. His height had increased to 197 cm. MRI showed an invasive mass measuring 56.2 × 58.1 × 45.0 mm, with compression of optic chiasma, bilateral cavernous sinus invasion, and hydrocephalus. His thyrotrope, corticotrope, and gonadotrope axes were deficient. Surgery, somatostatin analogs, and cabergoline did not control vertical growth and pegvisomant was added, although vertical growth continues (currently 207 cm at 11 years 7 months of age). X-LAG syndrome is a new genomic disorder in which early-onset pituitary tumorigenesis can lead to marked overgrowth and gigantism. This case illustrates the aggressive nature of tumor evolution and the challenging clinical management in X-LAG syndrome.
Keywords: Adenoma; Child; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Pituitary Neoplasms; Treatment Outcome

ALG1-CDG: Clinical and Molecular Characterization of 39 Unreported Patients. - Ng, Bobby G; Shiryaev, Sergey A; Rymen, Daisy; Eklund, Erik A; Raymond, Kimiyo; Kircher, Martin; Abdenur, Jose E; Alehan, Fusun; Midro, Alina T; Bamshad, Michael J; Barone, Rita; Berry, Gerard T; et al. (Hum Mutat, 2016)
Congenital disorders of glycosylation (CDG) arise from pathogenic mutations in over 100 genes leading to impaired protein or lipid glycosylation. ALG1 encodes a β1,4 mannosyltransferase that catalyzes the addition of the first of nine mannose moieties to form a dolichol-lipid linked oligosaccharide intermediate required for proper N-linked glycosylation. ALG1 mutations cause a rare autosomal recessive disorder termed ALG1-CDG. To date 13 mutations in 18 patients from 14 families have been described with varying degrees of clinical severity. We identified and characterized 39 previously unreported cases of ALG1-CDG from 32 families and add 26 new mutations. Pathogenicity of each mutation was confirmed based on its inability to rescue impaired growth or hypoglycosylation of a standard biomarker in an alg1-deficient yeast strain. Using this approach we could not establish a rank order comparison of biomarker glycosylation and patient phenotype, but we identified mutations with a lethal outcome in the first two years of life. The recently identified protein-linked xeno-tetrasaccharide biomarker, NeuAc-Gal-GlcNAc2 , was seen in all 27 patients tested. Our study triples the number of known patients and expands the molecular and clinical correlates of this disorder.
Keywords: Biomarkers; Congenital Disorders of Glycosylation; Female; Genes, Lethal; Glycosylation; Humans; Male; Mannosyltransferases; Mutation; Polysaccharides; Sequence Analysis, DNA; Survival Analysis

Asprosin, a Fasting-Induced Glucogenic Protein Hormone. - Romere, Chase; Duerrschmid, Clemens; Bournat, Juan; Constable, Petra; Jain, Mahim; Xia, Fan; Saha, Pradip K; Del Solar, Maria; Zhu, Bokai; York, Brian; Sarkar, Poonam; Rendon, David A; et al. (Cell, 2016)
Hepatic glucose release into the circulation is vital for brain function and survival during periods of fasting and is modulated by an array of hormones that precisely regulate plasma glucose levels. We have identified a fasting-induced protein hormone that modulates hepatic glucose release. It is the C-terminal cleavage product of profibrillin, and we name it Asprosin. Asprosin is secreted by white adipose, circulates at nanomolar levels, and is recruited to the liver, where it activates the G protein-cAMP-PKA pathway, resulting in rapid glucose release into the circulation. Humans and mice with insulin resistance show pathologically elevated plasma asprosin, and its loss of function via immunologic or genetic means has a profound glucose- and insulin-lowering effect secondary to reduced hepatic glucose release. Asprosin represents a glucogenic protein hormone, and therapeutically targeting it may be beneficial in type II diabetes and metabolic syndrome.
Keywords: Adipose Tissue, White; Amino Acid Sequence; Animals; Antibodies; Circadian Rhythm; Cyclic AMP; Cyclic AMP-Dependent Protein Kinases; Fasting; Female; Fetal Growth Retardation; Glucose; Humans; Insulin; Liver; Male; Mice; Mice, Inbred C57BL; Mice, Obese; Microfilament Proteins; Molecular Sequence Data; Peptide Fragments; Peptide Hormones; Progeria; Recombinant Proteins; Sequence Alignment

Assessment of estimated retinal atrophy progression in Stargardt macular dystrophy using spectral-domain optical coherence tomography. - Strauss, Rupert W; Muñoz, Beatriz; Wolfson, Yulia; Sophie, Raafay; Fletcher, Emily; Bittencourt, Millena G; Scholl, Hendrik P N (Br J Ophthalmol, 2016)
AIMS: To estimate disease progression based on analysis of macular volume measured by spectral-domain optical coherence tomography (SD-OCT) in patients affected by Stargardt macular dystrophy (STGD1) and to evaluate the influence of software errors on these measurements. METHODS: 58 eyes of 29 STGD1 patients were included. Numbers and types of algorithm errors were recorded and manually corrected. In a subgroup of 36 eyes of 18 patients with at least two examinations over time, total macular volume (TMV) and volumes of all nine Early Treatment of Diabetic Retinopathy Study (ETDRS) subfields were obtained. Random effects models were used to estimate the rate of change per year for the population, and empirical Bayes slopes were used to estimate yearly decline in TMV for individual eyes. RESULTS: 6958 single B-scans from 190 macular cube scans were analysed. 2360 (33.9%) showed algorithm errors. Mean observation period for follow-up data was 15 months (range 3-40). The median (IQR) change in TMV using the empirical Bayes estimates for the individual eyes was -0.103 (-0.145, -0.059) mm per year. The mean (±SD) TMV was 6.321±1.000 mm at baseline, and rate of decline was -0.118 mm per year (p=0.003). Yearly mean volume change was -0.004 mm in the central subfield (mean baseline=0.128 mm), -0.032 mm in the inner (mean baseline=1.484 mm) and -0.079 mm in the outer ETDRS subfields (mean baseline=5.206 mm). CONCLUSIONS: SD-OCT measurements allow monitoring the decline in retinal volume in STGD1; however, they require significant manual correction of software errors.
Keywords: Adolescent; Adult; Aged; Child; Disease Progression; Female; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Reproducibility of Results; Retrospective Studies; Tomography, Optical Coherence; Visual Acuity; Young Adult

Association Between Absolute Neutrophil Count and Variation at TCIRG1: The NHLBI Exome Sequencing Project. - Rosenthal, Elisabeth A; Makaryan, Vahagn; Burt, Amber A; Crosslin, David R; Kim, Daniel Seung; Smith, Joshua D; Nickerson, Deborah A; Reiner, Alex P; Rich, Stephen S; Jackson, Rebecca D; Ganesh, Santhi K; Polfus, Linda M; et al. (Genet Epidemiol, 2016)
Neutrophils are a key component of innate immunity. Individuals with low neutrophil count are susceptible to frequent infections. Linkage and association between congenital neutropenia and a single rare missense variant in TCIRG1 have been reported in a single family. Here, we report on nine rare missense variants at evolutionarily conserved sites in TCIRG1 that are associated with lower absolute neutrophil count (ANC; p = 0.005) in 1,058 participants from three cohorts: Atherosclerosis Risk in Communities (ARIC), Coronary Artery Risk Development in Young Adults (CARDIA), and Jackson Heart Study (JHS) of the NHLBI Grand Opportunity Exome Sequencing Project (GO ESP). These results validate the effects of TCIRG1 coding variation on ANC and suggest that this gene may be associated with a spectrum of mild to severe effects on ANC.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Cohort Studies; Female; Gene Frequency; Genotype; High-Throughput Nucleotide Sequencing; Humans; Leukocyte Count; Male; Middle Aged; Mutation, Missense; National Heart, Lung, and Blood Institute (U.S.); Neutropenia; Neutrophils; Sequence Analysis, DNA; United States; Vacuolar Proton-Translocating ATPases

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Ataxia-Pancytopenia Syndrome Is Caused by Missense Mutations in SAMD9L. - Chen, Dong-Hui; Below, Jennifer E; Shimamura, Akiko; Keel, Sioban B; Matsushita, Mark; Wolff, John; Sul, Youngmee; Bonkowski, Emily; Castella, Maria; Taniguchi, Toshiyasu; Nickerson, Deborah; Papayannopoulou, Thalia; et al. (Am J Hum Genet, 2016)
Ataxia-pancytopenia (AP) syndrome is characterized by cerebellar ataxia, variable hematologic cytopenias, and predisposition to marrow failure and myeloid leukemia, sometimes associated with monosomy 7. Here, in the four-generation family UW-AP, linkage analysis revealed four regions that provided the maximal LOD scores possible, one of which was in a commonly microdeleted chromosome 7q region. Exome sequencing identified a missense mutation (c.2640C>A, p.His880Gln) in the sterile alpha motif domain containing 9-like gene (SAMD9L) that completely cosegregated with disease. By targeted sequencing of SAMD9L, we subsequently identified a different missense mutation (c.3587G>C, p.Cys1196Ser) in affected members of the first described family with AP syndrome, Li-AP. Neither variant is reported in the public databases, both affect highly conserved amino acid residues, and both are predicted to be damaging. With time in culture, lymphoblastic cell lines (LCLs) from two affected individuals in family UW-AP exhibited copy-neutral loss of heterozygosity for large portions of the long arm of chromosome 7, resulting in retention of only the wild-type SAMD9L allele. Newly established LCLs from both individuals demonstrated the same phenomenon. In addition, targeted capture and sequencing of SAMD9L in uncultured blood DNA from both individuals showed bias toward the wild-type allele. These observations indicate in vivo hematopoietic mosaicism. The hematopoietic cytopenias that characterize AP syndrome and the selective advantage for clones that have lost the mutant allele support the postulated role of SAMD9L in the regulation of cell proliferation. Furthermore, we show that AP syndrome is distinct from the dyskeratoses congenita telomeropathies, with which it shares some clinical characteristics.
Keywords: Adolescent; Adult; Cerebellar Ataxia; Child; Chromosome Aberrations; Chromosomes, Human, Pair 7; Exome; Female; Genetic Linkage; Genotype; High-Throughput Nucleotide Sequencing; Humans; Intracellular Signaling Peptides and Proteins; Loss of Heterozygosity; Male; Middle Aged; Mutation, Missense; Pancytopenia; Pedigree; Proteins; Tumor Suppressor Proteins; Young Adult

Autosomal-Recessive Hearing Impairment Due to Rare Missense Variants within S1PR2. - Santos-Cortez, Regie Lyn P; Faridi, Rabia; Rehman, Atteeq U; Lee, Kwanghyuk; Ansar, Muhammad; Wang, Xin; Morell, Robert J; Isaacson, Rivka; Belyantseva, Inna A; Dai, Hang; Acharya, Anushree; Qaiser, Tanveer A; et al. (Am J Hum Genet, 2016)
The sphingosine-1-phosphate receptors (S1PRs) are a well-studied class of transmembrane G protein-coupled sphingolipid receptors that mediate multiple cellular processes. However, S1PRs have not been previously reported to be involved in the genetic etiology of human traits. S1PR2 lies within the autosomal-recessive nonsyndromic hearing impairment (ARNSHI) locus DFNB68 on 19p13.2. From exome sequence data we identified two pathogenic S1PR2 variants, c.323G>C (p.Arg108Pro) and c.419A>G (p.Tyr140Cys). Each of these variants co-segregates with congenital profound hearing impairment in consanguineous Pakistani families with maximum LOD scores of 6.4 for family DEM4154 and 3.3 for family PKDF1400. Neither S1PR2 missense variant was reported among ∼120,000 chromosomes in the Exome Aggregation Consortium database, in 76 unrelated Pakistani exomes, or in 720 Pakistani control chromosomes. Both DNA variants affect highly conserved residues of S1PR2 and are predicted to be damaging by multiple bioinformatics tools. Molecular modeling predicts that these variants affect binding of sphingosine-1-phosphate (p.Arg108Pro) and G protein docking (p.Tyr140Cys). In the previously reported S1pr2(-/-) mice, stria vascularis abnormalities, organ of Corti degeneration, and profound hearing loss were observed. Additionally, hair cell defects were seen in both knockout mice and morphant zebrafish. Family PKDF1400 presents with ARNSHI, which is consistent with the lack of gross malformations in S1pr2(-/-) mice, whereas family DEM4154 has lower limb malformations in addition to hearing loss. Our findings suggest the possibility of developing therapies against hair cell damage (e.g., from ototoxic drugs) through targeted stimulation of S1PR2.
Keywords: Amino Acid Sequence; Asian Continental Ancestry Group; Chromosomes, Human, Pair 19; Exome; Genes, Recessive; Hearing Loss; Humans; Lod Score; Logistic Models; Lysophospholipids; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Pedigree; Phenotype; Receptors, Lysosphingolipid; Sphingosine

Biallelic Mutations in Citron Kinase Link Mitotic Cytokinesis to Human Primary Microcephaly. - Li, Hongda; Bielas, Stephanie L; Zaki, Maha S; Ismail, Samira; Farfara, Dorit; Um, Kyongmi; Rosti, Rasim O; Scott, Eric C; Tu, Shu; Chi, Neil C; Gabriel, Stacey; Erson-Omay, Emine Z; et al. (Am J Hum Genet, 2016)
Cell division terminates with cytokinesis and cellular separation. Autosomal-recessive primary microcephaly (MCPH) is a neurodevelopmental disorder characterized by a reduction in brain and head size at birth in addition to non-progressive intellectual disability. MCPH is genetically heterogeneous, and 16 loci are known to be associated with loss-of-function mutations predominantly affecting centrosomal-associated proteins, but the multiple roles of centrosomes in cellular function has left questions about etiology. Here, we identified three families affected by homozygous missense mutations in CIT, encoding citron rho-interacting kinase (CIT), which has established roles in cytokinesis. All mutations caused substitution of conserved amino acid residues in the kinase domain and impaired kinase activity. Neural progenitors that were differentiated from induced pluripotent stem cells (iPSCs) derived from individuals with these mutations exhibited abnormal cytokinesis with delayed mitosis, multipolar spindles, and increased apoptosis, rescued by CRISPR/Cas9 genome editing. Our results highlight the importance of cytokinesis in the pathology of primary microcephaly.
Keywords: Alleles; Apoptosis; Centrosome; Child; Child, Preschool; Cytokinesis; Female; Genes, Recessive; Humans; Infant, Newborn; Intracellular Signaling Peptides and Proteins; Male; Microcephaly; Mitosis; Mutation, Missense; Pedigree; Protein Serine-Threonine Kinases

Bi-allelic Mutations in PKD1L1 Are Associated with Laterality Defects in Humans. - Vetrini, Francesco; D'Alessandro, Lisa C A; Akdemir, Zeynep C; Braxton, Alicia; Azamian, Mahshid S; Eldomery, Mohammad K; Miller, Kathryn; Kois, Chelsea; Sack, Virginia; Shur, Natasha; Rijhsinghani, Asha; Chandarana, Jignesh; et al. (Am J Hum Genet, 2016)
Disruption of the establishment of left-right (L-R) asymmetry leads to situs anomalies ranging from situs inversus totalis (SIT) to situs ambiguus (heterotaxy). The genetic causes of laterality defects in humans are highly heterogeneous. Via whole-exome sequencing (WES), we identified homozygous mutations in PKD1L1 from three affected individuals in two unrelated families. PKD1L1 encodes a polycystin-1-like protein and its loss of function is known to cause laterality defects in mouse and medaka fish models. Family 1 had one fetus and one deceased child with heterotaxy and complex congenital heart malformations. WES identified a homozygous splicing mutation, c.6473+2_6473+3delTG, which disrupts the invariant splice donor site in intron 42, in both affected individuals. In the second family, a homozygous c.5072G>C (p.Cys1691Ser) missense mutation was detected in an individual with SIT and congenital heart disease. The p.Cys1691Ser substitution affects a highly conserved cysteine residue and is predicted by molecular modeling to disrupt a disulfide bridge essential for the proper folding of the G protein-coupled receptor proteolytic site (GPS) motif. Damaging effects associated with substitutions of this conserved cysteine residue in the GPS motif have also been reported in other genes, namely GPR56, BAI3, and PKD1 in human and lat-1 in C. elegans, further supporting the likely pathogenicity of p.Cys1691Ser in PKD1L1. The identification of bi-allelic PKD1L1 mutations recapitulates previous findings regarding phenotypic consequences of loss of function of the orthologous genes in mice and medaka fish and further expands our understanding of genetic contributions to laterality defects in humans.
Keywords: Alleles; Amino Acid Motifs; Amino Acid Sequence; Animals; Caenorhabditis elegans; Cysteine; Exome; Female; Fetal Diseases; Functional Laterality; Heart Defects, Congenital; Heterotaxy Syndrome; Homozygote; Humans; Infant, Newborn; Introns; Male; Membrane Proteins; Mice; Middle Aged; Models, Molecular; Mutation; Mutation, Missense; Oryzias; Pedigree; RNA Splicing; Situs Inversus

Biallelic Mutations in TMTC3, Encoding a Transmembrane and TPR-Containing Protein, Lead to Cobblestone Lissencephaly. - Jerber, Julie; Zaki, Maha S; Al-Aama, Jumana Y; Rosti, Rasim Ozgur; Ben-Omran, Tawfeg; Dikoglu, Esra; Silhavy, Jennifer L; Caglar, Caner; Musaev, Damir; Albrecht, Beate; Campbell, Kevin P; Willer, Tobias; et al. (Am J Hum Genet, 2016)
Cobblestone lissencephaly (COB) is a severe brain malformation in which overmigration of neurons and glial cells into the arachnoid space results in the formation of cortical dysplasia. COB occurs in a wide range of genetic disorders known as dystroglycanopathies, which are congenital muscular dystrophies associated with brain and eye anomalies and range from Walker-Warburg syndrome to Fukuyama congenital muscular dystrophy. Each of these conditions has been associated with alpha-dystroglycan defects or with mutations in genes encoding basement membrane components, which are known to interact with alpha-dystroglycan. Our screening of a cohort of 25 families with recessive forms of COB identified six families affected by biallelic mutations in TMTC3 (encoding transmembrane and tetratricopeptide repeat containing 3), a gene without obvious functional connections to alpha-dystroglycan. Most affected individuals showed brainstem and cerebellum hypoplasia, as well as ventriculomegaly. However, the minority of the affected individuals had eye defects or elevated muscle creatine phosphokinase, separating the TMTC3 COB phenotype from typical congenital muscular dystrophies. Our data suggest that loss of TMTC3 causes COB with minimal eye or muscle involvement.
Keywords: Alleles; Amino Acid Sequence; Basement Membrane; Brain; Carrier Proteins; Cerebellum; Cobblestone Lissencephaly; Developmental Disabilities; Dystroglycans; Eye Abnormalities; Female; Humans; Infant; Male; Membrane Proteins; Mutation; Nervous System Malformations; Neuroglia; Neurons; Pedigree; Phenotype

Biallelic Mutations in UNC80 Cause Persistent Hypotonia, Encephalopathy, Growth Retardation, and Severe Intellectual Disability. - Stray-Pedersen, Asbjørg; Cobben, Jan-Maarten; Prescott, Trine E; Lee, Sora; Cang, Chunlei; Aranda, Kimberly; Ahmed, Sohnee; Alders, Marielle; Gerstner, Thorsten; Aslaksen, Kathinka; Tétreault, Martine; Qin, Wen; et al. (Am J Hum Genet, 2016)
Ion channel proteins are required for both the establishment of resting membrane potentials and the generation of action potentials. Hundreds of mutations in genes encoding voltage-gated ion channels responsible for action potential generation have been found to cause severe neurological diseases. In contrast, the roles of voltage-independent "leak" channels, important for the establishment and maintenance of resting membrane potentials upon which action potentials are generated, are not well established in human disease. UNC80 is a large component of the NALCN sodium-leak channel complex that regulates the basal excitability of the nervous system. Loss-of-function mutations of NALCN cause infantile hypotonia with psychomotor retardation and characteristic facies (IHPRF). We report four individuals from three unrelated families who have homozygous missense or compound heterozygous truncating mutations in UNC80 and persistent hypotonia, encephalopathy, growth failure, and severe intellectual disability. Compared to control cells, HEK293T cells transfected with an expression plasmid containing the c.5098C>T (p.Pro1700Ser) UNC80 mutation found in one individual showed markedly decreased NALCN channel currents. Our findings demonstrate the fundamental significance of UNC80 and basal ionic conductance to human health.
Keywords: Adolescent; Alleles; Brain Diseases; Carrier Proteins; Child; Child, Preschool; Female; Growth Disorders; Humans; Intellectual Disability; Membrane Proteins; Muscle Hypotonia; Mutation; Severity of Illness Index

Characterization of Greater Middle Eastern genetic variation for enhanced disease gene discovery. - Scott, Eric M; Halees, Anason; Itan, Yuval; Spencer, Emily G; He, Yupeng; Azab, Mostafa Abdellateef; Gabriel, Stacey B; Belkadi, Aziz; Boisson, Bertrand; Abel, Laurent; Clark, Andrew G; Alkuraya, Fowzan S; et al. (Nat Genet, 2016)
The Greater Middle East (GME) has been a central hub of human migration and population admixture. The tradition of consanguinity, variably practiced in the Persian Gulf region, North Africa, and Central Asia, has resulted in an elevated burden of recessive disease. Here we generated a whole-exome GME variome from 1,111 unrelated subjects. We detected substantial diversity and admixture in continental and subregional populations, corresponding to several ancient founder populations with little evidence of bottlenecks. Measured consanguinity rates were an order of magnitude above those in other sampled populations, and the GME population exhibited an increased burden of runs of homozygosity (ROHs) but showed no evidence for reduced burden of deleterious variation due to classically theorized 'genetic purging'. Applying this database to unsolved recessive conditions in the GME population reduced the number of potential disease-causing variants by four- to sevenfold. These results show variegated genetic architecture in GME populations and support future human genetic discoveries in Mendelian and population genetics.
Keywords: Asian Continental Ancestry Group; Cohort Studies; Consanguinity; Disease; European Continental Ancestry Group; Exome; Genes, Recessive; Genetic Markers; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Homozygote; Human Migration; Humans; Middle East

Chimeric transcripts resulting from complex duplications in chromosome Xq28. - Zuccherato, Luciana W; Alleva, Benjamin; Whiters, Marjorie A; Carvalho, Claudia M B; Lupski, James R (Hum Genet, 2016)
Gene fusions have been observed in somatic alterations in cancer and in schizophrenia. However, the underlying mechanism(s) for their formation are poorly understood. We experimentally demonstrated the expression of splicing variants of in silico predicted chimeric genes F8/CSAG1 and BCAP31/TEX28 in two individuals with de novo complex genomic rearrangements of Xq28; F8/CSAG1 includes exonization of an ERVL-MaLR intronic repetitive element. We provide evidence that replicative repair may contribute to exon shuffling processes and diversify the repertoire of expressed transcripts.
Keywords: Antigens, Neoplasm; Base Sequence; Cell Line; Chromosomes, Human, X; Exons; Gene Duplication; Gene Expression Regulation; Gene Rearrangement; Humans; Introns; Male; Membrane Proteins; Molecular Sequence Data; Neoplasm Proteins; RNA Splicing; RNA, Messenger; Transcription, Genetic

The ciliopathy-associated CPLANE proteins direct basal body recruitment of intraflagellar transport machinery. - Toriyama, Michinori; Lee, Chanjae; Taylor, S Paige; Duran, Ivan; Cohn, Daniel H; Bruel, Ange-Line; Tabler, Jacqueline M; Drew, Kevin; Kelly, Marcus R; Kim, Sukyoung; Park, Tae Joo; Braun, Daniela A; et al. (Nat Genet, 2016)
Cilia use microtubule-based intraflagellar transport (IFT) to organize intercellular signaling. Ciliopathies are a spectrum of human diseases resulting from defects in cilia structure or function. The mechanisms regulating the assembly of ciliary multiprotein complexes and the transport of these complexes to the base of cilia remain largely unknown. Combining proteomics, in vivo imaging and genetic analysis of proteins linked to planar cell polarity (Inturned, Fuzzy and Wdpcp), we identified and characterized a new genetic module, which we term CPLANE (ciliogenesis and planar polarity effector), and an extensive associated protein network. CPLANE proteins physically and functionally interact with the poorly understood ciliopathy-associated protein Jbts17 at basal bodies, where they act to recruit a specific subset of IFT-A proteins. In the absence of CPLANE, defective IFT-A particles enter the axoneme and IFT-B trafficking is severely perturbed. Accordingly, mutation of CPLANE genes elicits specific ciliopathy phenotypes in mouse models and is associated with ciliopathies in human patients.
Keywords: Animals; Ciliopathies; Flagella; Humans; Mice; Mutation; Phenotype; Protein Binding; Protein Transport; Proteins

Clinical genomics: from a truly personal genome viewpoint. - Lupski, James R (Hum Genet, 2016)
The path to Clinical Genomics is punctuated by our understanding of what types of DNA structural and sequence variation contribute to disease, the many technical challenges to detect such variation genome-wide, and the initial struggles to interpret personal genome variation in the context of disease. This review describes one perspective of the development of clinical genomics; whereas the experimental challenges, and hurdles to overcoming them, might be deemed readily apparent, the non-technical issues for clinical implementation may be less obvious. Some of these latter challenges, including: (1) informed consent, (2) privacy, (3) what constitutes potentially pathogenic variation contributing to disease, (4) disease penetrance in populations, and (5) the genetic architecture of disease, and the struggles sometimes faced for solutions, are highlighted using illustrative examples.
Keywords: Genetic Diseases, Inborn; Genetic Variation; Genome, Human; Genomics; Humans; Informed Consent; Precision Medicine; Privacy; Sequence Analysis, DNA

Collapsing glomerulopathy in a young woman with APOL1 risk alleles following acute parvovirus B19 infection: a case report investigation. - Besse, Whitney; Mansour, Sherry; Jatwani, Karan; Nast, Cynthia C; Brewster, Ursula C (BMC Nephrol, 2016)
BACKGROUND: Collapsing Glomerulopathy (CG), also known as the collapsing variant of Focal Segmental Glomerulosclerosis (FSGS), is distinct in both its clinical severity and its pathophysiologic characteristics from other forms of FSGS. This lesion occurs disproportionally in patients carrying two APOL1 risk alleles, and is the classic histologic lesion resulting from Human Immunodeficiency Virus (HIV) infection of podocytes. Other viral infections, including parvovirus B19, and drugs such as interferon that perturb the immune system, have also been associated with CG. Despite significant advances, explaining such genetic and immune/infectious associations with causative mechanisms and supporting evidence has proven challenging. CASE PRESENTATION: We report the case of a healthy (HIV-negative) pregnant 36 year-old Caribbean-American woman who presented with nephrotic syndrome and fetal demise in the setting of acute parvovirus B19 infection. A series of three renal biopsies and rapid clinical course showed progression from significant podocyte injury with mild light microscopy findings to classic viral-associated CG to ESRD in less than 3 months. Genetic analysis revealed two APOL1 G1 risk alleles. CONCLUSIONS: This is the first published case report of CG in the setting of acute parvovirus infection in a patient with two APOL1 risk allelles, and parvoviral proteins identified in renal epithelium on kidney biopsy. These findings support the causative role of parvovirus B19 infection in the development of CG on the background of APOL1 genetic risk.
Keywords: Acute Disease; Adult; Alleles; Apolipoprotein L1; Female; Glomerulosclerosis, Focal Segmental; Humans; Kidney Failure, Chronic; Parvoviridae Infections; Parvovirus B19, Human; Pregnancy; Pregnancy Complications, Infectious

Comparison of Short-Wavelength Reduced-Illuminance and Conventional Autofluorescence Imaging in Stargardt Macular Dystrophy. - Strauss, Rupert W; Muñoz, Beatriz; Jha, Anamika; Ho, Alexander; Cideciyan, Artur V; Kasilian, Melissa L; Wolfson, Yulia; Sadda, SriniVas; West, Sheila; Scholl, Hendrik P N; Michaelides, Michel (Am J Ophthalmol, 2016)
PURPOSE: To compare grading results between short-wavelength reduced-illuminance and conventional autofluorescence imaging in Stargardt macular dystrophy. DESIGN: Reliability study. METHODS: setting: Moorfields Eye Hospital, London (United Kingdom). PATIENTS: Eighteen patients (18 eyes) with Stargardt macular dystrophy. OBSERVATION PROCEDURES: A series of 3 fundus autofluorescence images using 3 different acquisition parameters on a custom-patched device were obtained: (1) 25% laser power and total sensitivity 87; (2) 25% laser power and freely adjusted sensitivity; and (3) 100% laser power and freely adjusted total sensitivity (conventional). The total area of 2 hypoautofluorescent lesion types (definitely decreased autofluorescence and poorly demarcated questionably decreased autofluorescence) was measured. MAIN OUTCOME MEASURES: Agreement in grading between the 3 imaging methods was assessed by kappa coefficients (κ) and intraclass correlation coefficients. RESULTS: The mean ± standard deviation area for images acquired with 25% laser power and freely adjusted total sensitivity was 2.04 ± 1.87 mm(2) for definitely decreased autofluorescence (n = 15) and 1.86 ± 2.14 mm(2) for poorly demarcated questionably decreased autofluorescence (n = 12). The intraclass correlation coefficient (95% confidence interval) was 0.964 (0.929, 0.999) for definitely decreased autofluorescence and 0.268 (0.000, 0.730) for poorly demarcated questionably decreased autofluorescence. CONCLUSIONS: Short-wavelength reduced-illuminance and conventional fundus autofluorescence imaging showed good concordance in assessing areas of definitely decreased autofluorescence. However, there was significantly higher variability between imaging modalities for assessing areas of poorly demarcated questionably decreased autofluorescence.
Keywords: Adult; Female; Fluorescein Angiography; Fundus Oculi; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Ophthalmoscopy; Optical Imaging; Reproducibility of Results; Stargardt Disease

Complex inheritance of ABCA4 disease: four mutations in a family with multiple macular phenotypes. - Lee, Winston; Xie, Yajing; Zernant, Jana; Yuan, Bo; Bearelly, Srilaxmi; Tsang, Stephen H; Lupski, James R; Allikmets, Rando (Hum Genet, 2016)
Over 800 mutations in the ABCA4 gene cause autosomal recessive Stargardt disease. Due to extensive genetic heterogeneity, observed variant-associated phenotypes can manifest tremendous variability of expression. Furthermore, the high carrier frequency of pathogenic ABCA4 alleles in the general population (~1:20) often results in pseudo-dominant inheritance patterns further complicating the diagnosis and characterization of affected individuals. This study describes a genotype/phenotype analysis of an unusual family with multiple macular disease phenotypes spanning across two generations and segregating four distinct ABCA4 mutant alleles. Complete sequencing of ABCA4 discovered two known missense mutations, p.C54Y and p.G1961E. Array comparative genomic hybridization revealed a large novel deletion combined with a small insertion, c.6148-698_c.6670del/insTGTGCACCTCCCTAG, and complete sequencing of the entire ABCA4 genomic locus uncovered a new deep intronic variant, c.302+68C>T. Patients with the p.G1961E mutation had the mildest, confined maculopathy phenotype with peripheral flecks while those with all other mutant allele combinations exhibited a more advanced stage of generalized retinal and choriocapillaris atrophy. This family epitomizes the clinical and genetic complexity of ABCA4-associated diseases. It contained variants from all classes of mutations, in the coding region, deep intronic, both single nucleotide variants and copy number variants that accounted for varying phenotypes segregating in an apparent dominant fashion. Unequivocally defining disease-associated alleles in the ABCA4 locus requires a multifaceted approach that includes advanced mutation detection methods and a thorough analysis of clinical phenotypes.
Keywords: Adult; Aged; ATP-Binding Cassette Transporters; Comparative Genomic Hybridization; DNA Copy Number Variations; Electroretinography; Female; High-Throughput Nucleotide Sequencing; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Mutation; Pedigree; Phenotype

Congenital nephrotic syndrome in an infant with ALG1-congenital disorder of glycosylation. - Harshman, Lyndsay A; Ng, Bobby G; Freeze, Hudson H; Trapane, Pamela; Dolezal, Anna; Brophy, Patrick D; Brumbaugh, Jane E (Pediatr Int, 2016)
Congenital nephrotic syndrome (NS) in the newborn is most frequently related to mutations in genes specific for structural integrity of the glomerular basement membrane and associated filtration structures within the kidney, resulting in massive leakage of plasma proteins into the urine. Occurrence of congenital NS in a multi-system syndrome is less common. We describe the case of an infant with deteriorating neurological status, seizures, edema, and proteinuria who was found to have a mutation in gene ALG1 and a renal biopsy consistent with congenital NS. Furthermore, we briefly review rare existing case reports documenting congenital NS in patients with mutations in ALG1, and treatment strategies, including novel use of peritoneal dialysis.
Keywords: Abnormalities, Multiple; Congenital Disorders of Glycosylation; DNA; DNA Mutational Analysis; Glycosylation; Humans; Infant, Newborn; Male; Mannosyltransferases; Mutation; Nephrotic Syndrome; Peritoneal Dialysis

Copy number analysis of the low-copy repeats at the primate NPHP1 locus by array comparative genomic hybridization. - Yuan, Bo; Liu, Pengfei; Rogers, Jeffrey; Lupski, James R (Genom Data, 2016)
Array comparative genomic hybridization (aCGH) has been widely used to detect copy number variants (CNVs) in both research and clinical settings. A customizable aCGH platform may greatly facilitate copy number analyses in genomic regions with higher-order complexity, such as low-copy repeats (LCRs). Here we present the aCGH analyses focusing on the 45 kb LCRs [1] at the NPHP1 region with diverse copy numbers in humans. Also, the interspecies aCGH analysis comparing human and nonhuman primates revealed dynamic copy number transitions of the human 45 kb LCR orthologues during primate evolution and therefore shed light on the origin of complexity at this locus. The original aCGH data are available at GEO under GSE73962.

Copy-Number Variation Contributes to the Mutational Load of Bardet-Biedl Syndrome. - Lindstrand, Anna; Frangakis, Stephan; Carvalho, Claudia M B; Richardson, Ellen B; McFadden, Kelsey A; Willer, Jason R; Pehlivan, Davut; Liu, Pengfei; Pediaditakis, Igor L; Sabo, Aniko; Lewis, Richard Alan; Banin, Eyal; et al. (Am J Hum Genet, 2016)
Bardet-Biedl syndrome (BBS) is a defining ciliopathy, notable for extensive allelic and genetic heterogeneity, almost all of which has been identified through sequencing. Recent data have suggested that copy-number variants (CNVs) also contribute to BBS. We used a custom oligonucleotide array comparative genomic hybridization (aCGH) covering 20 genes that encode intraflagellar transport (IFT) components and 74 ciliopathy loci to screen 92 unrelated individuals with BBS, irrespective of their known mutational burden. We identified 17 individuals with exon-disruptive CNVs (18.5%), including 13 different deletions in eight BBS genes (BBS1, BBS2, ARL6/BBS3, BBS4, BBS5, BBS7, BBS9, and NPHP1) and a deletion and a duplication in other ciliopathy-associated genes (ALMS1 and NPHP4, respectively). By contrast, we found a single heterozygous exon-disruptive event in a BBS-associated gene (BBS9) in 229 control subjects. Superimposing these data with resequencing revealed CNVs to (1) be sufficient to cause disease, (2) Mendelize heterozygous deleterious alleles, and (3) contribute oligogenic alleles by combining point mutations and exonic CNVs in multiple genes. Finally, we report a deletion and a splice site mutation in IFT74, inherited under a recessive paradigm, defining a candidate BBS locus. Our data suggest that CNVs contribute pathogenic alleles to a substantial fraction of BBS-affected individuals and highlight how either deletions or point mutations in discrete splice isoforms can induce hypomorphic mutations in genes otherwise intolerant to deleterious variation. Our data also suggest that CNV analyses and resequencing studies unbiased for previous mutational burden is necessary to delineate the complexity of disease architecture.
Keywords: Adolescent; Adult; Alleles; Animals; Bardet-Biedl Syndrome; Child; Child, Preschool; Chromosome Breakpoints; Cytoskeletal Proteins; DNA Copy Number Variations; Exons; Female; Gastrulation; Genes, Recessive; Humans; Infant; Male; Mutation; Pedigree; Young Adult; Zebrafish; Zebrafish Proteins

Cutaneous skeletal hypophosphatemia syndrome (CSHS) is a multilineage somatic mosaic RASopathy. - Lim, Young H; Ovejero, Diana; Derrick, Kristina M; Collins, Michael T; Choate, Keith A (J Am Acad Dermatol, 2016)
BACKGROUND: We recently demonstrated multilineage somatic mosaicism in cutaneous skeletal hypophosphatemia syndrome (CSHS), which features epidermal or melanocytic nevi, elevated fibroblast growth factor (FGF)-23, and hypophosphatemia, finding identical RAS mutations in affected skin and bone. OBJECTIVE: We sought to: (1) provide an updated overview of CSHS; (2) review its pathobiology; (3) present a new patient with CSHS; and (4) discuss treatment modalities. METHODS: We searched PubMed for "nevus AND rickets," and "nevus AND hypophosphatemia," identifying cases of nevi with hypophosphatemic rickets or elevated serum FGF-23. For our additional patient with CSHS, we performed histopathologic and radiographic surveys of skin and skeletal lesions, respectively. Sequencing was performed for HRAS, KRAS, and NRAS to determine causative mutations. RESULTS: Our new case harbored somatic activating HRAS p.G13 R mutation in affected tissue, consistent with previous findings. Although the mechanism of FGF-23 dysregulation is unknown in CSHS, interaction between FGF and MAPK pathways may provide insight into pathobiology. Anti-FGF-23 antibody KRN-23 may be useful in managing CSHS. LIMITATIONS: Multilineage RAS mutation in CSHS was recently identified; further studies on mechanism are unavailable. CONCLUSION: Patients with nevi in association with skeletal disease should be evaluated for serum phosphate and FGF-23. Further studies investigating the role of RAS in FGF-23 regulation are needed.
Keywords: Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Fibroblast Growth Factor-23; Fibroblast Growth Factors; Genes, ras; Humans; Mosaicism; Nevus, Pigmented; Osteomalacia; Rickets, Hypophosphatemic; Skin Neoplasms; Syndrome

De Novo and Rare Variants at Multiple Loci Support the Oligogenic Origins of Atrioventricular Septal Heart Defects. - Priest, James R; Osoegawa, Kazutoyo; Mohammed, Nebil; Nanda, Vivek; Kundu, Ramendra; Schultz, Kathleen; Lammer, Edward J; Girirajan, Santhosh; Scheetz, Todd; Waggott, Daryl; Haddad, Francois; Reddy, Sushma; et al. (PLoS Genet, 2016)
Congenital heart disease (CHD) has a complex genetic etiology, and recent studies suggest that high penetrance de novo mutations may account for only a small fraction of disease. In a multi-institutional cohort surveyed by exome sequencing, combining analysis of 987 individuals (discovery cohort of 59 affected trios and 59 control trios, and a replication cohort of 100 affected singletons and 533 unaffected singletons) we observe variation at novel and known loci related to a specific cardiac malformation the atrioventricular septal defect (AVSD). In a primary analysis, by combining developmental coexpression networks with inheritance modeling, we identify a de novo mutation in the DNA binding domain of NR1D2 (p.R175W). We show that p.R175W changes the transcriptional activity of Nr1d2 using an in vitro transactivation model in HUVEC cells. Finally, we demonstrate previously unrecognized cardiovascular malformations in the Nr1d2tm1-Dgen knockout mouse. In secondary analyses we map genetic variation to protein-interaction networks suggesting a role for two collagen genes in AVSD, which we corroborate by burden testing in a second replication cohort of 100 AVSDs and 533 controls (p = 8.37e-08). Finally, we apply a rare-disease inheritance model to identify variation in genes previously associated with CHD (ZFPM2, NSD1, NOTCH1, VCAN, and MYH6), cardiac malformations in mouse models (ADAM17, CHRD, IFT140, PTPRJ, RYR1 and ATE1), and hypomorphic alleles of genes causing syndromic CHD (EHMT1, SRCAP, BBS2, NOTCH2, and KMT2D) in 14 of 59 trios, greatly exceeding variation in control trios without CHD (p = 9.60e-06). In total, 32% of trios carried at least one putatively disease-associated variant across 19 loci,suggesting that inherited and de novo variation across a heterogeneous group of loci may contribute to disease risk.
Keywords: Animals; Female; Heart Septal Defects; Heterozygote; Homozygote; Humans; Male; Mice; Mice, Knockout; Mutation; Pedigree

De novo missense variants in PPP1CB are associated with intellectual disability and congenital heart disease. - Ma, Lijiang; Bayram, Yavuz; McLaughlin, Heather M; Cho, Megan T; Krokosky, Alyson; Turner, Clesson E; Lindstrom, Kristin; Bupp, Caleb P; Mayberry, Katey; Mu, Weiyi; Bodurtha, Joann; Weinstein, Veronique; et al. (Hum Genet, 2016)
Intellectual disabilities are genetically heterogeneous and can be associated with congenital anomalies. Using whole-exome sequencing (WES), we identified five different de novo missense variants in the protein phosphatase-1 catalytic subunit beta (PPP1CB) gene in eight unrelated individuals who share an overlapping phenotype of dysmorphic features, macrocephaly, developmental delay or intellectual disability (ID), congenital heart disease, short stature, and skeletal and connective tissue abnormalities. Protein phosphatase-1 (PP1) is a serine/threonine-specific protein phosphatase involved in the dephosphorylation of a variety of proteins. The PPP1CB gene encodes a PP1 subunit that regulates the level of protein phosphorylation. All five altered amino acids we observed are highly conserved among the PP1 subunit family, and all are predicted to disrupt PP1 subunit binding and impair dephosphorylation. Our data suggest that our heterozygous de novo PPP1CB pathogenic variants are associated with syndromic intellectual disability.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Intellectual Disability; Male; Mutation, Missense; Phosphorylation; Protein Phosphatase 1

De Novo Mutations in SON Disrupt RNA Splicing of Genes Essential for Brain Development and Metabolism, Causing an Intellectual-Disability Syndrome. - Kim, Jung-Hyun; Shinde, Deepali N; Reijnders, Margot R F; Hauser, Natalie S; Belmonte, Rebecca L; Wilson, Gregory R; Bosch, Daniëlle G M; Bubulya, Paula A; Shashi, Vandana; Petrovski, Slavé; Stone, Joshua K; Park, Eun Young; et al. (Am J Hum Genet, 2016)
The overall understanding of the molecular etiologies of intellectual disability (ID) and developmental delay (DD) is increasing as next-generation sequencing technologies identify genetic variants in individuals with such disorders. However, detailed analyses conclusively confirming these variants, as well as the underlying molecular mechanisms explaining the diseases, are often lacking. Here, we report on an ID syndrome caused by de novo heterozygous loss-of-function (LoF) mutations in SON. The syndrome is characterized by ID and/or DD, malformations of the cerebral cortex, epilepsy, vision problems, musculoskeletal abnormalities, and congenital malformations. Knockdown of son in zebrafish resulted in severe malformation of the spine, brain, and eyes. Importantly, analyses of RNA from affected individuals revealed that genes critical for neuronal migration and cortex organization (TUBG1, FLNA, PNKP, WDR62, PSMD3, and HDAC6) and metabolism (PCK2, PFKL, IDH2, ACY1, and ADA) are significantly downregulated because of the accumulation of mis-spliced transcripts resulting from erroneous SON-mediated RNA splicing. Our data highlight SON as a master regulator governing neurodevelopment and demonstrate the importance of SON-mediated RNA splicing in human development.
Keywords: Animals; Brain; Developmental Disabilities; DNA-Binding Proteins; Eye Abnormalities; Female; Genes, Essential; Haploinsufficiency; Head; Heterozygote; Humans; Intellectual Disability; Male; Metabolic Diseases; Minor Histocompatibility Antigens; Mutation; Pedigree; RNA Splicing; RNA, Messenger; Spine; Syndrome; Zebrafish

The dentin phosphoprotein repeat region and inherited defects of dentin. - Yang, Jie; Kawasaki, Kazuhiko; Lee, Moses; Reid, Bryan M; Nunez, Stephanie M; Choi, Murim; Seymen, Figen; Koruyucu, Mine; Kasimoglu, Yelda; Estrella-Yuson, Ninna; Lin, Brent P J; Simmer, James P; et al. (Mol Genet Genomic Med, 2016)
Nonsyndromic dentin defects classified as type II dentin dysplasia and types II and III dentinogenesis imperfecta are caused by mutations in DSPP (dentin sialophosphoprotein). Most reported disease-causing DSPP mutations occur within the repetitive DPP (dentin phosphoprotein) coding sequence. We characterized the DPP sequences of five probands with inherited dentin defects using single molecule real-time (SMRT) DNA sequencing. Eight of the 10 sequences matched previously reported DPP length haplotypes and two were novel. Alignment with known DPP sequences showed 32 indels arranged in 36 different patterns. Sixteen of the 32 indels were not represented in more than one haplotype. The 25 haplotypes with confirmed indels were aligned to generate a tree that describes how the length variations might have evolved. Some indels were independently generated in multiple lines. A previously reported disease-causing DSPP mutation in Family 1 was confirmed and its position clarified (c.3135delC; p.Ser1045Argfs*269). A novel frameshift mutation (c.3504_3508dup; p.Asp1170Alafs*146) caused the dentin defects in Family 2. A COL1A2 (c.2027G>A or p.Gly676Asp) missense mutation, discovered by whole-exome sequencing, caused the dentin defects in Family 3. We conclude that SMRT sequencing characterizes the DPP repeat region without cloning and can improve our understanding of normal and pathological length variations in DSPP alleles.

Destabilization of the IFT-B cilia core complex due to mutations in IFT81 causes a Spectrum of Short-Rib Polydactyly Syndrome. - Duran, Ivan; Taylor, S Paige; Zhang, Wenjuan; Martin, Jorge; Forlenza, Kimberly N; Spiro, Rhonda P; Nickerson, Deborah A; Bamshad, Michael; Cohn, Daniel H; Krakow, Deborah (Sci Rep, 2016)
Short-rib polydactyly syndromes (SRPS) and Asphyxiating thoracic dystrophy (ATD) or Jeune Syndrome are recessively inherited skeletal ciliopathies characterized by profound skeletal abnormalities and are frequently associated with polydactyly and multiorgan system involvement. SRPS are produced by mutations in genes that participate in the formation and function of primary cilia and usually result from disruption of retrograde intraflagellar (IFT) transport of the cilium. Herein we describe a new spectrum of SRPS caused by mutations in the gene IFT81, a key component of the IFT-B complex essential for anterograde transport. In mutant chondrocytes, the mutations led to low levels of IFT81 and mutant cells produced elongated cilia, had altered hedgehog signaling, had increased post-translation modification of tubulin, and showed evidence of destabilization of additional anterograde transport complex components. These findings demonstrate the importance of IFT81 in the skeleton, its role in the anterograde transport complex, and expand the number of loci associated with SRPS.

Digenic mutations of human paralogs in Dent's disease type 2 associated with Chiari I malformation. - Duran, Daniel; Jin, Sheng Chih; DeSpenza, Tyrone; Nelson-Williams, Carol; Cogal, Andrea G; Abrash, Elizabeth W; Harris, Peter C; Lieske, John C; Shimshak, Serena Je; Mane, Shrikant; Bilguvar, Kaya; DiLuna, Michael L; et al. (Hum Genome Var, 2016)
and its paralog encode phosphatidylinositol 5-phosphatases that localize to the primary cilium and have roles in ciliogenesis. Mutations in cause the X-linked Dent disease type 2 (DD2; OMIM# 300555), characterized by low-molecular weight proteinuria, hypercalciuria, and the variable presence of cataracts, glaucoma and intellectual disability without structural brain anomalies. Disease-causing mutations in have not been described in humans. Here, we report the case of an 11-year-old boy with short stature and an above-average IQ; severe proteinuria, hypercalciuria and osteopenia resulting in a vertebral compression fracture; and Chiari I malformation with cervico-thoracic syringohydromyelia requiring suboccipital decompression. Sequencing revealed a novel, DD2-causing 462 bp deletion disrupting exon 3 of and a maternally inherited, extremely rare (ExAC allele frequency 8.4×10) damaging missense mutation in (p.A51V). This mutation substitutes an evolutionarily conserved amino acid in the protein's critical PH domain. analyses of mutation impact predicted by SIFT, PolyPhen2, MetaSVM and CADD algorithms were all highly deleterious. Together, our findings report a novel association of DD2 with Chiari I malformation and syringohydromyelia, and document the effects of digenic mutation of human paralogs. These findings lend genetic support to the hypothesis that impaired ciliogenesis may contribute to the development of Chiari I malformation, and implicates OCRL-dependent PIP metabolism in this mechanism.

Disrupted nitric oxide signaling due to GUCY1A3 mutations increases risk for moyamoya disease, achalasia and hypertension. - Wallace, S; Guo, D-C; Regalado, E; Mellor-Crummey, L; Bamshad, M; Nickerson, D A; Dauser, R; Hanchard, N; Marom, R; Martin, E; Berka, V; Sharina, I; et al. (Clin Genet, 2016)
Moyamoya disease (MMD) is a progressive vasculopathy characterized by occlusion of the terminal portion of the internal carotid arteries and its branches, and the formation of compensatory moyamoya collateral vessels. Homozygous mutations in GUCY1A3 have been reported as a cause of MMD and achalasia. Probands (n = 96) from unrelated families underwent sequencing of GUCY1A3. Functional studies were performed to confirm the pathogenicity of identified GUCY1A3 variants. Two affected individuals from the unrelated families were found to have compound heterozygous mutations in GUCY1A3. MM041 was diagnosed with achalasia at 4 years of age, hypertension and MMD at 18 years of age. MM149 was diagnosed with MMD and hypertension at the age of 20 months. Both individuals carry one allele that is predicted to lead to haploinsufficiency and a second allele that is predicted to produce a mutated protein. Biochemical studies of one of these alleles, GUCY1A3 Cys517Tyr, showed that the mutant protein (a subunit of soluble guanylate cyclase) has a significantly blunted signaling response with exposure to nitric oxide (NO). GUCY1A3 missense and haploinsufficiency mutations disrupt NO signaling leading to MMD and hypertension, with or without achalasia.
Keywords: Adolescent; Adult; Animals; Child; Child, Preschool; Cohort Studies; Esophageal Achalasia; Female; Humans; Hypertension; Infant; Male; Middle Aged; Moyamoya Disease; Mutation; Nitric Oxide; Nonlinear Dynamics; Regression Analysis; Sf9 Cells; Signal Transduction; Soluble Guanylyl Cyclase

Dominant de novo DSP mutations cause erythrokeratodermia-cardiomyopathy syndrome. - Boyden, Lynn M; Kam, Chen Y; Hernández-Martín, Angela; Zhou, Jing; Craiglow, Brittany G; Sidbury, Robert; Mathes, Erin F; Maguiness, Sheilagh M; Crumrine, Debra A; Williams, Mary L; Hu, Ronghua; Lifton, Richard P; et al. (Hum Mol Genet, 2016)
Disorders of keratinization (DOK) show marked genotypic and phenotypic heterogeneity. In most cases, disease is primarily cutaneous, and further clinical evaluation is therefore rarely pursued. We have identified subjects with a novel DOK featuring erythrokeratodermia and initially-asymptomatic, progressive, potentially fatal cardiomyopathy, a finding not previously associated with erythrokeratodermia. We show that de novo missense mutations clustered tightly within a single spectrin repeat of DSP cause this novel cardio-cutaneous disorder, which we term erythrokeratodermia-cardiomyopathy (EKC) syndrome. We demonstrate that DSP mutations in our EKC syndrome subjects affect localization of desmosomal proteins and connexin 43 in the skin, and result in desmosome aggregation, widening of intercellular spaces, and lipid secretory defects. DSP encodes desmoplakin, a primary component of desmosomes, intercellular adhesion junctions most abundant in the epidermis and heart. Though mutations in DSP are known to cause other disorders, our cohort features the unique clinical finding of severe whole-body erythrokeratodermia, with distinct effects on localization of desmosomal proteins and connexin 43. These findings add a severe, previously undescribed syndrome featuring erythrokeratodermia and cardiomyopathy to the spectrum of disease caused by mutation in DSP, and identify a specific region of the protein critical to the pathobiology of EKC syndrome and to DSP function in the heart and skin.
Keywords: Amino Acid Sequence; Cardiomyopathies; Child; Child, Preschool; Connexin 43; Desmoplakins; Desmosomes; Female; Humans; Infant; Male; Molecular Sequence Data; Mutation, Missense; Myocardium; Protein Transport; Sequence Alignment; Skin; Skin Diseases, Genetic; Syndrome

DVL3 Alleles Resulting in a -1 Frameshift of the Last Exon Mediate Autosomal-Dominant Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Hoischen, Alexander; Bayram, Yavuz; Withers, Marjorie; Gezdirici, Alper; Kimonis, Virginia; Steehouwer, Marloes; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; van Bon, Bregje W M; et al. (Am J Hum Genet, 2016)
Robinow syndrome is a rare congenital disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features. Recent reports have identified, in individuals with dominant Robinow syndrome, a specific type of variant characterized by being uniformly located in the penultimate exon of DVL1 and resulting in a -1 frameshift allele with a premature termination codon that escapes nonsense-mediated decay. Here, we studied a cohort of individuals who had been clinically diagnosed with Robinow syndrome but who had not received a molecular diagnosis from variant studies of DVL1, WNT5A, and ROR2. Because of the uniform location of frameshift variants in DVL1-mediated Robinow syndrome and the functional redundancy of DVL1, DVL2, and DVL3, we elected to pursue direct Sanger sequencing of the penultimate exon of DVL1 and its paralogs DVL2 and DVL3 to search for potential disease-associated variants. Remarkably, targeted sequencing identified five unrelated individuals harboring heterozygous, de novo frameshift variants in DVL3, including two splice acceptor mutations and three 1 bp deletions. Similar to the variants observed in DVL1-mediated Robinow syndrome, all variants in DVL3 result in a -1 frameshift, indicating that these highly specific alterations might be a common cause of dominant Robinow syndrome. Here, we review the current knowledge of these peculiar variant alleles in DVL1- and DVL3-mediated Robinow syndrome and further elucidate the phenotypic features present in subjects with DVL1 and DVL3 frameshift mutations.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Base Sequence; Codon, Nonsense; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exons; Female; Frameshift Mutation; Genetic Variation; Humans; Limb Deformities, Congenital; Male; Molecular Sequence Data; Phosphoproteins; Proto-Oncogene Proteins; Receptor Tyrosine Kinase-like Orphan Receptors; Sequence Analysis, DNA; Sequence Deletion; Urogenital Abnormalities; Wnt Proteins; Wnt-5a Protein

Evidence of macular pigment in the central macula in albinism. - Wolfson, Yulia; Fletcher, Emily; Strauss, Rupert W; Scholl, Hendrik P N (Exp Eye Res, 2016)
PURPOSE: Albinism represents a spectrum of disorders with diminished to absent amounts of melanin pigmentation including the posterior segment of the eye. Macular pigment (MP) consists of two main carotenoids, lutein and zeaxanthin, concentrated in the macula. MP serves as blue light absorbent, antioxidant, and may reduce chromatic aberration and glare. It remains unclear if albinos have detectable MP. The purpose was to investigate the distribution of MP in albino patients with psychophysical and imaging techniques. METHODS: MP was measured at the eccentricity of 0.5° by heterochromatic flicker perimetry (QuantifEye(®); Tinsley Precision Instruments Ltd.) or by scanning laser ophthalmoscopy (MPOD module, MultiColor Spectralis(®), Heidelberg Engineering, Heidelberg, Germany) in four albino patients, who were also investigated with multimodal ophthalmic imaging. RESULTS: Visual acuity ranged from 20/32 to 20/125, nystagmus was present in three patients, and all patients showed typical foveal hypoplasia on fundus exam and optical coherence tomography. Fundus autofluorescence (FAF) demonstrated various degrees of central FAF signal attenuation. Genetic testing was available in three patients and confirmed the diagnosis. Measurable amounts of MP were detected in all four patients and ranged from 0.05 to 0.24, which is below the normal range. CONCLUSIONS: We conclude that MP can be demonstrated and measured in albinos. Further studies are needed to investigate MP accumulation following carotenoid supplementation and its impact on visual performance.
Keywords: Adult; Aged; Albinism, Ocular; Fluorescein Angiography; Humans; Macula Lutea; Macular Pigment; Male; Middle Aged; Tomography, Optical Coherence; Visual Acuity; Visual Field Tests; Visual Fields

Exome Sequencing Analysis in Severe, Early-Onset Chronic Obstructive Pulmonary Disease. - Qiao, Dandi; Lange, Christoph; Beaty, Terri H; Crapo, James D; Barnes, Kathleen C; Bamshad, Michael; Hersh, Craig P; Morrow, Jarrett; Pinto-Plata, Victor M; Marchetti, Nathaniel; Bueno, Raphael; Celli, Bartolome R; et al. (Am J Respir Crit Care Med, 2016)
RATIONALE: Genomic regions identified by genome-wide association studies explain only a small fraction of heritability for chronic obstructive pulmonary disease (COPD). Alpha-1 antitrypsin deficiency shows that rare coding variants of large effect also influence COPD susceptibility. We hypothesized that exome sequencing in families identified through a proband with severe, early-onset COPD would identify additional rare genetic determinants of large effect. OBJECTIVES: To identify rare genetic determinants of severe COPD. METHODS: We applied filtering approaches to identify potential causal variants for COPD in whole exomes from 347 subjects in 49 extended pedigrees from the Boston Early-Onset COPD Study. We assessed the power of this approach under different levels of genetic heterogeneity using simulations. We tested genes identified in these families using gene-based association tests in exomes of 204 cases with severe COPD and 195 resistant smokers from the COPDGene study. In addition, we examined previously described loci associated with COPD using these datasets. MEASUREMENTS AND MAIN RESULTS: We identified 69 genes with predicted deleterious nonsynonymous, stop, or splice variants that segregated with severe COPD in at least two pedigrees. Four genes (DNAH8, ALCAM, RARS, and GBF1) also demonstrated an increase in rare nonsynonymous, stop, and/or splice mutations in cases compared with resistant smokers from the COPDGene study; however, these results were not statistically significant. We demonstrate the limitations of the power of this approach under genetic heterogeneity through simulation. CONCLUSIONS: Rare deleterious coding variants may increase risk for COPD, but multiple genes likely contribute to COPD susceptibility.
Keywords: Adult; alpha 1-Antitrypsin Deficiency; Boston; Exome; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Pulmonary Disease, Chronic Obstructive; Severity of Illness Index

Exome sequencing identifies a de novo frameshift mutation in the imprinted gene ZDBF2 in a sporadic patient with Nasopalpebral Lipoma-coloboma syndrome. - Chacón-Camacho, Oscar F; Sobreira, Nara; You, Jing; Piña-Aguilar, Raul E; Villegas-Ruiz, Vanessa; Zenteno, Juan C (Am J Med Genet A, 2016)
Nasopalpebral lipoma-coloboma syndrome (NPLCS, OMIM%167730) is an uncommon malformation entity with autosomal dominant inheritance characterized by the combination of nasopalpebral lipoma, colobomas in upper and lower eyelids, telecanthus, and maxillary hypoplasia. To date, no genetic defects have been associated with familial or sporadic NPLCS cases and the etiology of the disease remains unknown. In this work, the results of whole exome sequencing in a sporadic NPLCS patient are presented. Exome sequencing identified a de novo heterozygous frameshift dinucleotide insertion c.6245_6246 insTT (p.His2082fs*67) in ZDBF2 (zinc finger, DBF-type containing 2), a gene located at 2q33.3. This variant was absent in parental DNA, in a set of 300 ethnically matched controls, and in public exome variant databases. This is the first genetic variant identified in a NPLCS patient and evidence supporting the pathogenicity of the identified mutation is discussed. © 2016 Wiley Periodicals, Inc.
Keywords: Abnormalities, Multiple; Base Sequence; Child, Preschool; Coloboma; DNA-Binding Proteins; Exome; Eyelid Neoplasms; Female; Frameshift Mutation; Genomic Imprinting; Humans; Lipoma; Pedigree

Exome Sequencing Identifies Biallelic MSH3 Germline Mutations as a Recessive Subtype of Colorectal Adenomatous Polyposis. - Adam, Ronja; Spier, Isabel; Zhao, Bixiao; Kloth, Michael; Marquez, Jonathan; Hinrichsen, Inga; Kirfel, Jutta; Tafazzoli, Aylar; Horpaopan, Sukanya; Uhlhaas, Siegfried; Stienen, Dietlinde; Friedrichs, Nicolaus; et al. (Am J Hum Genet, 2016)
In ∼30% of families affected by colorectal adenomatous polyposis, no germline mutations have been identified in the previously implicated genes APC, MUTYH, POLE, POLD1, and NTHL1, although a hereditary etiology is likely. To uncover further genes with high-penetrance causative mutations, we performed exome sequencing of leukocyte DNA from 102 unrelated individuals with unexplained adenomatous polyposis. We identified two unrelated individuals with differing compound-heterozygous loss-of-function (LoF) germline mutations in the mismatch-repair gene MSH3. The impact of the MSH3 mutations (c.1148delA, c.2319-1G>A, c.2760delC, and c.3001-2A>C) was indicated at the RNA and protein levels. Analysis of the diseased individuals' tumor tissue demonstrated high microsatellite instability of di- and tetranucleotides (EMAST), and immunohistochemical staining illustrated a complete loss of nuclear MSH3 in normal and tumor tissue, confirming the LoF effect and causal relevance of the mutations. The pedigrees, genotypes, and frequency of MSH3 mutations in the general population are consistent with an autosomal-recessive mode of inheritance. Both index persons have an affected sibling carrying the same mutations. The tumor spectrum in these four persons comprised colorectal and duodenal adenomas, colorectal cancer, gastric cancer, and an early-onset astrocytoma. Additionally, we detected one unrelated individual with biallelic PMS2 germline mutations, representing constitutional mismatch-repair deficiency. Potentially causative variants in 14 more candidate genes identified in 26 other individuals require further workup. In the present study, we identified biallelic germline MSH3 mutations in individuals with a suspected hereditary tumor syndrome. Our data suggest that MSH3 mutations represent an additional recessive subtype of colorectal adenomatous polyposis.
Keywords: Adenomatous Polyposis Coli; Adolescent; Adult; Alleles; Child, Preschool; Colorectal Neoplasms; DNA Mutational Analysis; DNA-Binding Proteins; Exome; Female; Genes, Recessive; Germ-Line Mutation; Humans; Male; Middle Aged; Mismatch Repair Endonuclease PMS2; MutS Homolog 3 Protein; Pedigree

Exome sequencing identifies potential novel candidate genes in patients with unexplained colorectal adenomatous polyposis. - Spier, Isabel; Kerick, Martin; Drichel, Dmitriy; Horpaopan, Sukanya; Altmüller, Janine; Laner, Andreas; Holzapfel, Stefanie; Peters, Sophia; Adam, Ronja; Zhao, Bixiao; Becker, Tim; Lifton, Richard P; et al. (Fam Cancer, 2016)
In up to 30% of patients with colorectal adenomatous polyposis, no germline mutation in the known genes APC, causing familial adenomatous polyposis, MUTYH, causing MUTYH-associated polyposis, and POLE or POLD1, causing Polymerase-Proofreading-associated polyposis can be identified, although a hereditary etiology is likely. To uncover new causative genes, exome sequencing was performed using DNA from leukocytes and a total of 12 colorectal adenomas from seven unrelated patients with unexplained sporadic adenomatous polyposis. For data analysis and variant filtering, an established bioinformatics pipeline including in-house tools was applied. Variants were filtered for rare truncating point mutations and copy-number variants assuming a dominant, recessive, or tumor suppressor model of inheritance. Subsequently, targeted sequence analysis of the most promising candidate genes was performed in a validation cohort of 191 unrelated patients. All relevant variants were validated by Sanger sequencing. The analysis of exome sequencing data resulted in the identification of rare loss-of-function germline mutations in three promising candidate genes (DSC2, PIEZO1, ZSWIM7). In the validation cohort, further variants predicted to be pathogenic were identified in DSC2 and PIEZO1. According to the somatic mutation spectra, the adenomas in this patient cohort follow the classical pathways of colorectal tumorigenesis. The present study identified three candidate genes which might represent rare causes for a predisposition to colorectal adenoma formation. Especially PIEZO1 (FAM38A) and ZSWIM7 (SWS1) warrant further exploration. To evaluate the clinical relevance of these genes, investigation of larger patient cohorts and functional studies are required.
Keywords: Adenomatous Polyposis Coli; Adenomatous Polyps; Aged; Desmocollins; Exome; Female; Genetic Predisposition to Disease; Germ-Line Mutation; High-Throughput Nucleotide Sequencing; Humans; Ion Channels; Male; Middle Aged; Reproducibility of Results

Exome sequencing in mostly consanguineous Arab families with neurologic disease provides a high potential molecular diagnosis rate. - Charng, Wu-Lin; Karaca, Ender; Coban Akdemir, Zeynep; Gambin, Tomasz; Atik, Mehmed M; Gu, Shen; Posey, Jennifer E; Jhangiani, Shalini N; Muzny, Donna M; Doddapaneni, Harsha; Hu, Jianhong; Boerwinkle, Eric; et al. (BMC Med Genomics, 2016)
BACKGROUND: Neurodevelopment is orchestrated by a wide range of genes, and the genetic causes of neurodevelopmental disorders are thus heterogeneous. We applied whole exome sequencing (WES) for molecular diagnosis and in silico analysis to identify novel disease gene candidates in a cohort from Saudi Arabia with primarily Mendelian neurologic diseases. METHODS: We performed WES in 31 mostly consanguineous Arab families and analyzed both single nucleotide and copy number variants (CNVs) from WES data. Interaction/expression network and pathway analyses, as well as paralog studies were utilized to investigate potential pathogenicity and disease association of novel candidate genes. Additional cases for candidate genes were identified through the clinical WES database at Baylor Miraca Genetics Laboratories and GeneMatcher. RESULTS: We found known pathogenic or novel variants in known disease genes with phenotypic expansion in 6 families, disease-associated CNVs in 2 families, and 12 novel disease gene candidates in 11 families, including KIF5B, GRM7, FOXP4, MLLT1, and KDM2B. Overall, a potential molecular diagnosis was provided by variants in known disease genes in 17 families (54.8 %) and by novel candidate disease genes in an additional 11 families, making the potential molecular diagnostic rate ~90 %. CONCLUSIONS: Molecular diagnostic rate from WES is improved by exome-predicted CNVs. Novel candidate disease gene discovery is facilitated by paralog studies and through the use of informatics tools and available databases to identify additional evidence for pathogenicity. TRIAL REGISTRATION: Not applicable.
Keywords: Arabs; Cohort Studies; Consanguinity; Data Mining; Databases, Genetic; DNA Copy Number Variations; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Diagnostic Techniques; Nervous System Diseases; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Expansion of the spectrum of ITGB6-related disorders to adolescent alopecia, dentogingival abnormalities and intellectual disability. - Ansar, Muhammad; Jan, Abid; Santos-Cortez, Regie Lyn P; Wang, Xin; Suliman, Muhammad; Acharya, Anushree; Habib, Rabia; Abbe, Izoduwa; Ali, Ghazanfar; Lee, Kwanghyuk; Smith, Joshua D; Nickerson, Deborah A; et al. (Eur J Hum Genet, 2016)
Alopecia with mental retardation (APMR) is a very rare disorder. In this study, we report on a consanguineous Pakistani family (AP91) with mild-to-moderate intellectual disability, adolescent alopecia and dentogingival abnormalities. Using homozygosity mapping, linkage analysis and exome sequencing, we identified a novel rare missense variant c.898G>A (p.(Glu300Lys)) in ITGB6, which co-segregates with the phenotype within the family and is predicted to be deleterious. Structural modeling shows that Glu300 lies in the β-propeller domain, and is surrounded by several residues that are important for heterodimerization with α integrin. Previous studies showed that ITGB6 variants can cause amelogenesis imperfecta in humans, but patients from family AP91 who are homozygous for the c.898G>A variant present with neurological and dermatological features, indicating a role for ITGB6 beyond enamel formation. Our study demonstrates that a rare deleterious variant within ITGB6 causes not only dentogingival anomalies but also intellectual disability and alopecia.
Keywords: Adolescent; Adult; Alopecia; Child; Female; Humans; Integrin beta Chains; Intellectual Disability; Male; Mutation, Missense; Pedigree; Phenotype; Protein Domains; Syndrome; Tooth Abnormalities

Family Based Whole Exome Sequencing Reveals the Multifaceted Role of Notch Signaling in Congenital Heart Disease. - Preuss, Christoph; Capredon, Melanie; Wünnemann, Florian; Chetaille, Philippe; Prince, Andrea; Godard, Beatrice; Leclerc, Severine; Sobreira, Nara; Ling, Hua; Awadalla, Philip; Thibeault, Maryse; Khairy, Paul; et al. (PLoS Genet, 2016)
Left-ventricular outflow tract obstructions (LVOTO) encompass a wide spectrum of phenotypically heterogeneous heart malformations which frequently cluster in families. We performed family based whole-exome and targeted re-sequencing on 182 individuals from 51 families with multiple affected members. Central to our approach is the family unit which serves as a reference to identify causal genotype-phenotype correlations. Screening a multitude of 10 overlapping phenotypes revealed disease associated and co-segregating variants in 12 families. These rare or novel protein altering mutations cluster predominantly in genes (NOTCH1, ARHGAP31, MAML1, SMARCA4, JARID2, JAG1) along the Notch signaling cascade. This is in line with a significant enrichment (Wilcoxon, p< 0.05) of variants with a higher pathogenicity in the Notch signaling pathway in patients compared to controls. The significant enrichment of novel protein truncating and missense mutations in NOTCH1 highlights the allelic and phenotypic heterogeneity in our pediatric cohort. We identified novel co-segregating pathogenic mutations in NOTCH1 associated with left and right-sided cardiac malformations in three independent families with a total of 15 affected individuals. In summary, our results suggest that a small but highly pathogenic fraction of family specific mutations along the Notch cascade are a common cause of LVOTO.
Keywords: Aortic Valve; Codon, Nonsense; Constriction, Pathologic; Exome; Female; Genetic Association Studies; Genetic Linkage; Genome, Human; Heart Defects, Congenital; Humans; Male; Pedigree; Receptor, Notch1; Receptors, Notch; Sequence Deletion; Signal Transduction; Ventricular Outflow Obstruction

Family-Based Rare Variant Association Analysis: A Fast and Efficient Method of Multivariate Phenotype Association Analysis. - Wang, Longfei; Lee, Sungyoung; Gim, Jungsoo; Qiao, Dandi; Cho, Michael; Elston, Robert C; Silverman, Edwin K; Won, Sungho (Genet Epidemiol, 2016)
Family-based designs have been repeatedly shown to be powerful in detecting the significant rare variants associated with human diseases. Furthermore, human diseases are often defined by the outcomes of multiple phenotypes, and thus we expect multivariate family-based analyses may be very efficient in detecting associations with rare variants. However, few statistical methods implementing this strategy have been developed for family-based designs. In this report, we describe one such implementation: the multivariate family-based rare variant association tool (mFARVAT). mFARVAT is a quasi-likelihood-based score test for rare variant association analysis with multiple phenotypes, and tests both homogeneous and heterogeneous effects of each variant on multiple phenotypes. Simulation results show that the proposed method is generally robust and efficient for various disease models, and we identify some promising candidate genes associated with chronic obstructive pulmonary disease. The software of mFARVAT is freely available at http://healthstat.snu.ac.kr/software/mfarvat/, implemented in C++ and supported on Linux and MS Windows.
Keywords: Computer Simulation; Genetic Association Studies; Genetic Variation; Humans; Likelihood Functions; Models, Genetic; Phenotype

FARVATX: Family-Based Rare Variant Association Test for X-Linked Genes. - Choi, Sungkyoung; Lee, Sungyoung; Qiao, Dandi; Hardin, Megan; Cho, Michael H; Silverman, Edwin K; Park, Taesung; Won, Sungho (Genet Epidemiol, 2016)
Although the X chromosome has many genes that are functionally related to human diseases, the complicated biological properties of the X chromosome have prevented efficient genetic association analyses, and only a few significantly associated X-linked variants have been reported for complex traits. For instance, dosage compensation of X-linked genes is often achieved via the inactivation of one allele in each X-linked variant in females; however, some X-linked variants can escape this X chromosome inactivation. Efficient genetic analyses cannot be conducted without prior knowledge about the gene expression process of X-linked variants, and misspecified information can lead to power loss. In this report, we propose new statistical methods for rare X-linked variant genetic association analysis of dichotomous phenotypes with family-based samples. The proposed methods are computationally efficient and can complete X-linked analyses within a few hours. Simulation studies demonstrate the statistical efficiency of the proposed methods, which were then applied to rare-variant association analysis of the X chromosome in chronic obstructive pulmonary disease. Some promising significant X-linked genes were identified, illustrating the practical importance of the proposed methods.
Keywords: Alleles; Chromosomes, Human, X; Female; Genes, X-Linked; Genetic Variation; Humans; Models, Genetic; Pedigree; Phenotype; X Chromosome Inactivation

FAT1 mutations cause a glomerulotubular nephropathy. - Gee, Heon Yung; Sadowski, Carolin E; Aggarwal, Pardeep K; Porath, Jonathan D; Yakulov, Toma A; Schueler, Markus; Lovric, Svjetlana; Ashraf, Shazia; Braun, Daniela A; Halbritter, Jan; Fang, Humphrey; Airik, Rannar; et al. (Nat Commun, 2016)
Steroid-resistant nephrotic syndrome (SRNS) causes 15% of chronic kidney disease (CKD). Here we show that recessive mutations in FAT1 cause a distinct renal disease entity in four families with a combination of SRNS, tubular ectasia, haematuria and facultative neurological involvement. Loss of FAT1 results in decreased cell adhesion and migration in fibroblasts and podocytes and the decreased migration is partially reversed by a RAC1/CDC42 activator. Podocyte-specific deletion of Fat1 in mice induces abnormal glomerular filtration barrier development, leading to podocyte foot process effacement. Knockdown of Fat1 in renal tubular cells reduces migration, decreases active RAC1 and CDC42, and induces defects in lumen formation. Knockdown of fat1 in zebrafish causes pronephric cysts, which is partially rescued by RAC1/CDC42 activators, confirming a role of the two small GTPases in the pathogenesis. These findings provide new insights into the pathogenesis of SRNS and tubulopathy, linking FAT1 and RAC1/CDC42 to podocyte and tubular cell function.
Keywords: Animals; Cadherins; cdc42 GTP-Binding Protein; Cell Adhesion; Cell Movement; Dilatation, Pathologic; Fibroblasts; Gene Knockdown Techniques; Hematuria; Humans; Kidney Tubules; Lissencephaly; Mice; Mutation; Nephrotic Syndrome; Podocytes; rac1 GTP-Binding Protein; Syndrome; Zebrafish; Zebrafish Proteins

FOXE3 mutations predispose to thoracic aortic aneurysms and dissections. - Kuang, Shao-Qing; Medina-Martinez, Olga; Guo, Dong-Chuan; Gong, Limin; Regalado, Ellen S; Reynolds, Corey L; Boileau, Catherine; Jondeau, Guillaume; Prakash, Siddharth K; Kwartler, Callie S; Zhu, Lawrence Yang; Peters, Andrew M; et al. (J Clin Invest, 2016)
The ascending thoracic aorta is designed to withstand biomechanical forces from pulsatile blood. Thoracic aortic aneurysms and acute aortic dissections (TAADs) occur as a result of genetically triggered defects in aortic structure and a dysfunctional response to these forces. Here, we describe mutations in the forkhead transcription factor FOXE3 that predispose mutation-bearing individuals to TAAD. We performed exome sequencing of a large family with multiple members with TAADs and identified a rare variant in FOXE3 with an altered amino acid in the DNA-binding domain (p.Asp153His) that segregated with disease in this family. Additional pathogenic FOXE3 variants were identified in unrelated TAAD families. In mice, Foxe3 deficiency reduced smooth muscle cell (SMC) density and impaired SMC differentiation in the ascending aorta. Foxe3 expression was induced in aortic SMCs after transverse aortic constriction, and Foxe3 deficiency increased SMC apoptosis and ascending aortic rupture with increased aortic pressure. These phenotypes were rescued by inhibiting p53 activity, either by administration of a p53 inhibitor (pifithrin-α), or by crossing Foxe3-/- mice with p53-/- mice. Our data demonstrate that FOXE3 mutations lead to a reduced number of aortic SMCs during development and increased SMC apoptosis in the ascending aorta in response to increased biomechanical forces, thus defining an additional molecular pathway that leads to familial thoracic aortic disease.
Keywords: Adult; Aneurysm, Dissecting; Animals; Aorta; Aortic Aneurysm, Thoracic; Apoptosis; Cells, Cultured; Cyclin-Dependent Kinase Inhibitor p21; Female; Forkhead Transcription Factors; Gene Expression; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Mice, Inbred C57BL; Mice, Knockout; Middle Aged; Muscle, Smooth, Vascular; Mutation, Missense; Myocytes, Smooth Muscle; Pedigree; Tumor Suppressor Protein p53; Vascular Remodeling; Zebrafish

Gene discovery for Mendelian conditions via social networking: de novo variants in KDM1A cause developmental delay and distinctive facial features. - Chong, Jessica X; Yu, Joon-Ho; Lorentzen, Peter; Park, Karen M; Jamal, Seema M; Tabor, Holly K; Rauch, Anita; Saenz, Margarita Sifuentes; Boltshauser, Eugen; Patterson, Karynne E; Nickerson, Deborah A; Bamshad, Michael J (Genet Med, 2016)
PURPOSE: The pace of Mendelian gene discovery is slowed by the "n-of-1 problem"-the difficulty of establishing the causality of a putatively pathogenic variant in a single person or family. Identification of an unrelated person with an overlapping phenotype and suspected pathogenic variant in the same gene can overcome this barrier, but it is often impeded by lack of a convenient or widely available way to share data on candidate variants/genes among families, clinicians, and researchers. METHODS: Social networking among families, clinicians, and researchers was used to identify three children with variants of unknown significance in KDM1A and similar phenotypes. RESULTS: De novo variants in KDM1A underlie a new syndrome characterized by developmental delay and distinctive facial features. CONCLUSION: Social networking is a potentially powerful strategy to discover genes for rare Mendelian conditions, particularly those with nonspecific phenotypic features. To facilitate the efforts of families to share phenotypic and genomic information with each other, clinicians, and researchers, we developed the Repository for Mendelian Genomics Family Portal (RMD-FP; http://uwcmg.org/#/family). Design and development of MyGene2 (http://www.mygene2.org), a Web-based tool that enables families, clinicians, and researchers to search for gene matches based on analysis of phenotype and exome data deposited into the RMD-FP, is under way.Genet Med 18 8, 788-795.
Keywords: Child; Child, Preschool; Databases, Factual; Developmental Disabilities; Female; Genetic Association Studies; Histone Demethylases; Humans; Information Dissemination; Male; Mutation, Missense; Phenotype; Social Networking; Web Browser

Genetic Candidate Variants in Two Multigenerational Families with Childhood Apraxia of Speech. - Peter, Beate; Wijsman, Ellen M; Nato, Alejandro Q; Matsushita, Mark M; Chapman, Kathy L; Stanaway, Ian B; Wolff, John; Oda, Kaori; Gabo, Virginia B; Raskind, Wendy H (PLoS One, 2016)
Childhood apraxia of speech (CAS) is a severe and socially debilitating form of speech sound disorder with suspected genetic involvement, but the genetic etiology is not yet well understood. Very few known or putative causal genes have been identified to date, e.g., FOXP2 and BCL11A. Building a knowledge base of the genetic etiology of CAS will make it possible to identify infants at genetic risk and motivate the development of effective very early intervention programs. We investigated the genetic etiology of CAS in two large multigenerational families with familial CAS. Complementary genomic methods included Markov chain Monte Carlo linkage analysis, copy-number analysis, identity-by-descent sharing, and exome sequencing with variant filtering. No overlaps in regions with positive evidence of linkage between the two families were found. In one family, linkage analysis detected two chromosomal regions of interest, 5p15.1-p14.1, and 17p13.1-q11.1, inherited separately from the two founders. Single-point linkage analysis of selected variants identified CDH18 as a primary gene of interest and additionally, MYO10, NIPBL, GLP2R, NCOR1, FLCN, SMCR8, NEK8, and ANKRD12, possibly with additive effects. Linkage analysis in the second family detected five regions with LOD scores approaching the highest values possible in the family. A gene of interest was C4orf21 (ZGRF1) on 4q25-q28.2. Evidence for previously described causal copy-number variations and validated or suspected genes was not found. Results are consistent with a heterogeneous CAS etiology, as is expected in many neurogenic disorders. Future studies will investigate genome variants in these and other families with CAS.
Keywords: Apraxias; DNA Copy Number Variations; Exome; Female; Genetic Linkage; Genetic Predisposition to Disease; Genotype; Humans; Lod Score; Male; Pedigree; Risk; Speech

Genome-Wide Association and Exome Sequencing Study of Language Disorder in an Isolated Population. - Kornilov, Sergey A; Rakhlin, Natalia; Koposov, Roman; Lee, Maria; Yrigollen, Carolyn; Çağlayan, Ahmet Okay; Magnuson, James S; Mane, Shrikant; Chang, Joseph T; Grigorenko, Elena L (Pediatrics, 2016)
BACKGROUND AND OBJECTIVE: Developmental language disorder (DLD) is a highly prevalent neurodevelopmental disorder associated with negative outcomes in different domains; the etiology of DLD is unknown. To investigate the genetic underpinnings of DLD, we performed genome-wide association and whole exome sequencing studies in a geographically isolated population with a substantially elevated prevalence of the disorder (ie, the AZ sample). METHODS: DNA samples were collected from 359 individuals for the genome-wide association study and from 12 severely affected individuals for whole exome sequencing. Multifaceted phenotypes, representing major domains of expressive language functioning, were derived from collected speech samples. RESULTS: Gene-based analyses revealed a significant association between SETBP1 and complexity of linguistic output (P = 5.47 × 10(-7)). The analysis of exome variants revealed coding sequence variants in 14 genes, most of which play a role in neural development. Targeted enrichment analysis implicated myocyte enhancer factor-2 (MEF2)-regulated genes in DLD in the AZ population. The main findings were successfully replicated in an independent cohort of children at risk for related disorders (n = 372). CONCLUSIONS: MEF2-regulated pathways were identified as potential candidate pathways in the etiology of DLD. Several genes (including the candidate SETBP1 and other MEF2-related genes) seem to jointly influence certain, but not all, facets of the DLD phenotype. Even when genetic and environmental diversity is reduced, DLD is best conceptualized as etiologically complex. Future research should establish whether the signals detected in the AZ population can be replicated in other samples and languages and provide further characterization of the identified pathway.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Child; Child, Preschool; Exome; Genome-Wide Association Study; Humans; Language Disorders; Middle Aged; Polymorphism, Single Nucleotide; Russia; Sequence Analysis, DNA; Young Adult

A genome-wide association study of congenital cardiovascular left-sided lesions shows association with a locus on chromosome 20. - Hanchard, Neil A; Swaminathan, Shanker; Bucasas, Kristine; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid S; Wang, Xueqing; Lewin, Mark; Towbin, Jeffrey A; D'Alessandro, Lisa C A; Morris, Shaine A; Dreyer, William; et al. (Hum Mol Genet, 2016)
Congenital heart defects involving left-sided lesions (LSLs) are relatively common birth defects with substantial morbidity and mortality. Previous studies have suggested a high heritability with a complex genetic architecture, such that only a few LSL loci have been identified. We performed a genome-wide case-control association study to address the role of common variants using a discovery cohort of 778 cases and 2756 controls. We identified a genome-wide significant association mapping to a 200 kb region on chromosome 20q11 [P= 1.72 × 10 for rs3746446; imputed Single Nucleotide Polymorphism (SNP) rs6088703 P= 3.01 × 10, odds ratio (OR)= 1.6 for both]. This result was supported by transmission disequilibrium analyses using a subset of 541 case families (lowest P in region= 4.51 × 10, OR= 1.5). Replication in a cohort of 367 LSL cases and 5159 controls showed nominal association (P= 0.03 for rs3746446) resulting in P= 9.49 × 10 for rs3746446 upon meta-analysis of the combined cohorts. In addition, a group of seven SNPs on chromosome 1q21.3 met threshold for suggestive association (lowest P= 9.35 × 10 for rs12045807). Both regions include genes involved in cardiac development-MYH7B/miR499A on chromosome 20 and CTSK, CTSS and ARNT on chromosome 1. Genome-wide heritability analysis using case-control genotyped SNPs suggested that the mean heritability of LSLs attributable to common variants is moderately high ([Formula: see text] range= 0.26-0.34) and consistent with previous assertions. These results provide evidence for the role of common variation in LSLs, proffer new genes as potential biological candidates, and give further insight to the complex genetic architecture of congenital heart disease.
Keywords: Chromosome Mapping; Chromosomes, Human, Pair 20; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Defects, Congenital; Heart Ventricles; Humans; Male; Polymorphism, Single Nucleotide

Germline De Novo Mutations in GNB1 Cause Severe Neurodevelopmental Disability, Hypotonia, and Seizures. - Petrovski, Slavé; Küry, Sébastien; Myers, Candace T; Anyane-Yeboa, Kwame; Cogné, Benjamin; Bialer, Martin; Xia, Fan; Hemati, Parisa; Riviello, James; Mehaffey, Michele; Besnard, Thomas; Becraft, Emily; et al. (Am J Hum Genet, 2016)
Whole-exome sequencing of 13 individuals with developmental delay commonly accompanied by abnormal muscle tone and seizures identified de novo missense mutations enriched within a sub-region of GNB1, a gene encoding the guanine nucleotide-binding protein subunit beta-1, Gβ. These 13 individuals were identified among a base of 5,855 individuals recruited for various undiagnosed genetic disorders. The probability of observing 13 or more de novo mutations by chance among 5,855 individuals is very low (p = 7.1 × 10(-21)), implicating GNB1 as a genome-wide-significant disease-associated gene. The majority of these 13 mutations affect known Gβ binding sites, which suggests that a likely disease mechanism is through the disruption of the protein interface required for Gα-Gβγ interaction (resulting in a constitutively active Gβγ) or through the disruption of residues relevant for interaction between Gβγ and certain downstream effectors (resulting in reduced interaction with the effectors). Strikingly, 8 of the 13 individuals recruited here for a neurodevelopmental disorder have a germline de novo GNB1 mutation that overlaps a set of five recurrent somatic tumor mutations for which recent functional studies demonstrated a gain-of-function effect due to constitutive activation of G protein downstream signaling cascades for some of the affected residues.
Keywords: Adolescent; Adult; Child; Child, Preschool; Developmental Disabilities; Exome; Female; Germ-Line Mutation; GTP-Binding Protein beta Subunits; Humans; Infant; Intellectual Disability; Male; Muscle Hypotonia; Phenotype; Protein Conformation; Seizures; Signal Transduction; Young Adult

A germline ERBB3 variant is a candidate for predisposition to erythroid MDS/erythroleukemia. - Braunstein, E M; Li, R; Sobreira, N; Marosy, B; Hetrick, K; Doheny, K; Gocke, C D; Valle, D; Brodsky, R A; Cheng, L (Leukemia, 2016)
Keywords: Adult; Aged; Female; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Leukemia, Erythroblastic, Acute; Male; Middle Aged; Myelodysplastic Syndromes; Pedigree; Receptor, ErbB-3

Germline or somatic GPR101 duplication leads to X-linked acrogigantism: a clinico-pathological and genetic study. - Iacovazzo, Donato; Caswell, Richard; Bunce, Benjamin; Jose, Sian; Yuan, Bo; Hernández-Ramírez, Laura C; Kapur, Sonal; Caimari, Francisca; Evanson, Jane; Ferraù, Francesco; Dang, Mary N; Gabrovska, Plamena; et al. (Acta Neuropathol Commun, 2016)
Non-syndromic pituitary gigantism can result from AIP mutations or the recently identified Xq26.3 microduplication causing X-linked acrogigantism (XLAG). Within Xq26.3, GPR101 is believed to be the causative gene, and the c.924G > C (p.E308D) variant in this orphan G protein-coupled receptor has been suggested to play a role in the pathogenesis of acromegaly.We studied 153 patients (58 females and 95 males) with pituitary gigantism. AIP mutation-negative cases were screened for GPR101 duplication through copy number variation droplet digital PCR and high-density aCGH. The genetic, clinical and histopathological features of XLAG patients were studied in detail. 395 peripheral blood and 193 pituitary tumor DNA samples from acromegaly patients were tested for GPR101 variants.We identified 12 patients (10 females and 2 males; 7.8 %) with XLAG. In one subject, the duplicated region only contained GPR101, but not the other three genes in found to be duplicated in the previously reported patients, defining a new smallest region of overlap of duplications. While females presented with germline mutations, the two male patients harbored the mutation in a mosaic state. Nine patients had pituitary adenomas, while three had hyperplasia. The comparison of the features of XLAG, AIP-positive and GPR101&AIP-negative patients revealed significant differences in sex distribution, age at onset, height, prolactin co-secretion and histological features. The pathological features of XLAG-related adenomas were remarkably similar. These tumors had a sinusoidal and lobular architecture. Sparsely and densely granulated somatotrophs were admixed with lactotrophs; follicle-like structures and calcifications were commonly observed. Patients with sporadic of familial acromegaly did not have an increased prevalence of the c.924G > C (p.E308D) GPR101 variant compared to public databases.In conclusion, XLAG can result from germline or somatic duplication of GPR101. Duplication of GPR101 alone is sufficient for the development of XLAG, implicating it as the causative gene within the Xq26.3 region. The pathological features of XLAG-associated pituitary adenomas are typical and, together with the clinical phenotype, should prompt genetic testing.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Female; Gene Duplication; Germ-Line Mutation; Gigantism; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Pituitary Neoplasms; Receptors, G-Protein-Coupled; Treatment Outcome; Young Adult

GNA14 Somatic Mutation Causes Congenital and Sporadic Vascular Tumors by MAPK Activation. - Lim, Young H; Bacchiocchi, Antonella; Qiu, Jingyao; Straub, Robert; Bruckner, Anna; Bercovitch, Lionel; Narayan, Deepak; McNiff, Jennifer; Ko, Christine; Robinson-Bostom, Leslie; Antaya, Richard; Halaban, Ruth; et al. (Am J Hum Genet, 2016)
Vascular tumors are among the most common neoplasms in infants and children; 5%-10% of newborns present with or develop lesions within the first 3 months of life. Most are benign infantile hemangiomas that typically regress by 5 years of age; other vascular tumors include congenital tufted angiomas (TAs), kaposiform hemangioendotheliomas (KHEs), and childhood lobular capillary hemangiomas (LCHs). Some of these lesions can become locally invasive and unresponsive to pharmacologic intervention, leading to significant complications. Recent investigation has revealed that activating mutations in HRAS, KRAS, NRAS, GNAQ, and GNA11 can cause certain types of rare childhood vascular tumors, and we have now identified causal recurrent somatic activating mutations in GNA14 by whole-exome and targeted sequencing. We found somatic activating GNA14 c.614A>T (p.Gln205Leu) mutations in one KHE, one TA, and one LCH and a GNA11 c.547C>T (p.Arg183Cys) mutation in two LCH lesions. We examined mutation pathobiology via expression of mutant GNA14 or GNA11 in primary human endothelial cells and melanocytes. GNA14 and GNA11 mutations induced changes in cellular morphology and rendered cells growth-factor independent by upregulating the MAPK pathway. Our findings identify GNA14 mutations as a cause of childhood vascular tumors, offer insight into mechanisms of oncogenic transformation by mutations affecting Gaq family members, and identify potential targets for therapeutic intervention.
Keywords: Cells, Cultured; Child, Preschool; Enzyme Activation; GTP-Binding Protein alpha Subunits; GTP-Binding Protein alpha Subunits, Gq-G11; Human Umbilical Vein Endothelial Cells; Humans; Infant; Infant, Newborn; Intercellular Signaling Peptides and Proteins; Male; MAP Kinase Signaling System; Melanocytes; Mitogen-Activated Protein Kinases; Mutation; Proto-Oncogene Proteins c-akt; Vascular Neoplasms

Gonadal mosaicism in ARID1B gene causes intellectual disability and dysmorphic features in three siblings. - Ben-Salem, Salma; Sobreira, Nara; Akawi, Nadia A; Al-Shamsi, Aisha M; John, Anne; Pramathan, Thachillath; Valle, David; Ali, Bassam R; Al-Gazali, Lihadh (Am J Med Genet A, 2016)
The gene encoding the AT-rich interaction domain-containing protein 1B (ARID1B) has recently been shown to be one of the most frequently mutated genes in patients with intellectual disability (ID). The phenotypic spectrums associated with variants in this gene vary widely ranging for mild to severe non-specific ID to Coffin-Siris syndrome. In this study, we evaluated three children from a consanguineous Emirati family affected with ID and dysmorphic features. Genomic DNA from all affected siblings was analyzed using CGH array and whole-exome sequencing (WES). Based on a recessive mode of inheritance, homozygous or compound heterozygous variants shared among all three affected children could not be identified. However, further analysis revealed a heterozygous variant (c.4318C>T; p.Q1440*) in the three affected children in an autosomal dominant ID causing gene, ARID1B. This variant was absent in peripheral blood samples obtained from both parents and unaffected siblings. Therefore, we propose that the most likely explanation for this situation is that one of the parents is a gonadal mosaic for the variant. To the best of our knowledge, this is the first report of a gonadal mosaicism inheritance of an ARID1B variant leading to familial ID recurrence.
Keywords: Abnormalities, Multiple; Adolescent; Child; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Mosaicism; Mutation; Neck; Pedigree; Siblings; Transcription Factors

Hutterite-type cataract maps to chromosome 6p21.32-p21.31, cosegregates with a homozygous mutation in LEMD2, and is associated with sudden cardiac death. - Boone, Philip M; Yuan, Bo; Gu, Shen; Ma, Zhiwei; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Jain, Mahim; Murdock, Todd J; White, Janson J; Jhangiani, Shalini N; Walker, Kimberly; Wang, Qiaoyan; et al. (Mol Genet Genomic Med, 2016)
BACKGROUND: Juvenile-onset cataracts are known among the Hutterites of North America. Despite being identified over 30 years ago, this autosomal recessive condition has not been mapped, and the disease gene is unknown. METHODS: We performed whole exome sequencing of three Hutterite-type cataract trios and follow-up genotyping and mapping in four extended kindreds. RESULTS: Trio exomes enabled genome-wide autozygosity mapping, which localized the disease gene to a 9.5-Mb region on chromosome 6p. This region contained two candidate variants, LEMD2 c.T38G and MUC21 c.665delC. Extended pedigrees recruited for variant genotyping revealed multiple additional relatives with juvenile-onset cataract, as well as six deceased relatives with both cataracts and sudden cardiac death. The candidate variants were genotyped in 84 family members, including 17 with cataracts; only the variant in LEMD2 cosegregated with cataracts (LOD = 9.62). SNP-based fine mapping within the 9.5 Mb linked region supported this finding by refining the cataract locus to a 0.5- to 2.9-Mb subregion (6p21.32-p21.31) containing LEMD2 but not MUC21. LEMD2 is expressed in mouse and human lenses and encodes a LEM domain-containing protein; the c.T38G missense mutation is predicted to mutate a highly conserved residue within this domain (p.Leu13Arg). CONCLUSION: We performed a genetic and genomic study of Hutterite-type cataract and found evidence for an association of this phenotype with sudden cardiac death. Using combined genetic and genomic approaches, we mapped cataracts to a small portion of chromosome 6 and propose that they result from a homozygous missense mutation in LEMD2.

Identification and clinical characterization of Hermansky-Pudlak syndrome alleles in the Pakistani population. - Yousaf, Sairah; Shahzad, Mohsin; Kausar, Tasleem; Sheikh, Shakeel A; Tariq, Nabeela; Shabbir, Asra S; Ali, Muhammad; Waryah, Ali M; Shaikh, Rehan S; Riazuddin, Saima; Ahmed, Zubair M (Pigment Cell Melanoma Res, 2016)
Keywords: Adolescent; Adult; Alleles; Child; Child, Preschool; Female; Hermanski-Pudlak Syndrome; Humans; Infant; Male; Membrane Proteins; Middle Aged; Pakistan; Pedigree

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics. - Loviglio, Maria Nicla; Beck, Christine R; White, Janson J; Leleu, Marion; Harel, Tamar; Guex, Nicolas; Niknejad, Anne; Bi, Weimin; Chen, Edward S; Crespo, Isaac; Yan, Jiong; Charng, Wu-Lin; et al. (Genome Med, 2016)
BACKGROUND: Smith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors. METHODS: We investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and biomedical text mining), transcriptomics, and circularized chromatin conformation capture (4C-seq) was applied to verify whether modified genes are part of the same disease network as known SMS-causing genes. RESULTS: Potentially deleterious variants were identified in nine of these individuals using whole-exome sequencing. Eight of these changes affect KMT2D, ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C, and POGZ, known to be associated with Kabuki syndrome 1, Mowat-Wilson syndrome, cardiofaciocutaneous syndrome, glycine encephalopathy, mental retardation and microcephaly with pontine and cerebellar hypoplasia, X-linked mental retardation 13, X-linked mental retardation Claes-Jensen type, and White-Sutton syndrome, respectively. The ninth individual carries a de novo variant in JAKMIP1, a regulator of neuronal translation that was recently found deleted in a patient with autism spectrum disorder. Analyses of co-expression and biomedical text mining suggest that these pathologies and SMS are part of the same disease network. Further support for this hypothesis was obtained from transcriptome profiling that showed that the expression levels of both Zeb2 and Map2k2 are perturbed in Rai1 mice. As an orthogonal approach to potentially contributory disease gene variants, we used chromatin conformation capture to reveal chromatin contacts between RAI1 and the loci flanking ZEB2 and GLDC, as well as between RAI1 and human orthologs of the genes that show perturbed expression in our Rai1 mouse model. CONCLUSIONS: These holistic studies of RAI1 and its interactions allow insights into SMS and other disorders associated with intellectual disability and behavioral abnormalities. Our findings support a pan-genomic approach to the molecular diagnosis of a distinctive disorder.
Keywords: Animals; Embryo, Mammalian; Exome; Female; Gene Regulatory Networks; Genomics; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors; Transcriptome

Identification of Intellectual Disability Genes in Female Patients with a Skewed X-Inactivation Pattern. - Fieremans, Nathalie; Van Esch, Hilde; Holvoet, Maureen; Van Goethem, Gert; Devriendt, Koenraad; Rosello, Monica; Mayo, Sonia; Martinez, Francisco; Jhangiani, Shalini; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; et al. (Hum Mutat, 2016)
Intellectual disability (ID) is a heterogeneous disorder with an unknown molecular etiology in many cases. Previously, X-linked ID (XLID) studies focused on males because of the hemizygous state of their X chromosome. Carrier females are generally unaffected because of the presence of a second normal allele, or inactivation of the mutant X chromosome in most of their cells (skewing). However, in female ID patients, we hypothesized that the presence of skewing of X-inactivation would be an indicator for an X chromosomal ID cause. We analyzed the X-inactivation patterns of 288 females with ID, and found that 22 (7.6%) had extreme skewing (>90%), which is significantly higher than observed in the general population (3.6%; P = 0.029). Whole-exome sequencing of 19 females with extreme skewing revealed causal variants in six females in the XLID genes DDX3X, NHS, WDR45, MECP2, and SMC1A. Interestingly, variants in genes escaping X-inactivation presumably cause both XLID and skewing of X-inactivation in three of these patients. Moreover, variants likely accounting for skewing only were detected in MED12, HDAC8, and TAF9B. All tested candidate causative variants were de novo events. Hence, extreme skewing is a good indicator for the presence of X-linked variants in female patients.
Keywords: Carrier Proteins; Cell Cycle Proteins; Chromosomal Proteins, Non-Histone; DEAD-box RNA Helicases; Exome; Female; Genetic Variation; Humans; Intellectual Disability; Methyl-CpG-Binding Protein 2; Nuclear Proteins; Sequence Analysis, DNA; X Chromosome Inactivation

Identification of Rare Variants in Metabolites of the Carnitine Pathway by Whole Genome Sequencing Analysis. - Yazdani, Akram; Yazdani, Azam; Liu, Xiaoming; Boerwinkle, Eric (Genet Epidemiol, 2016)
We use whole genome sequence data and rare variant analysis methods to investigate a subset of the human serum metabolome, including 16 carnitine-related metabolites that are important components of mammalian energy metabolism. Medium pass sequence data consisting of 12,820,347 rare variants and serum metabolomics data were available on 1,456 individuals. By applying a penalization method, we identified two genes FGF8 and MDGA2 with significant effects on lysine and cis-4-decenoylcarnitine, respectively, using Δ-AIC and likelihood ratio test statistics. Single variant analyses in these regions did not identify a single low-frequency variant (minor allele count > 3) responsible for the underlying signal. The results demonstrate the utility of whole genome sequence and innovative analyses for identifying candidate regions influencing complex phenotypes.
Keywords: Biomarkers; Carnitine; Female; Fibroblast Growth Factor 8; Genetic Variation; GPI-Linked Proteins; High-Throughput Nucleotide Sequencing; Humans; Linkage Disequilibrium; Lysine; Male; Metabolomics; Middle Aged; Neural Cell Adhesion Molecules; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Identifying Allosteric Hotspots with Dynamics: Application to Inter- and Intra-species Conservation. - Clarke, Declan; Sethi, Anurag; Li, Shantao; Kumar, Sushant; Chang, Richard W F; Chen, Jieming; Gerstein, Mark (Structure, 2016)
The rapidly growing volume of data being produced by next-generation sequencing initiatives is enabling more in-depth analyses of conservation than previously possible. Deep sequencing is uncovering disease loci and regions under selective constraint, despite the fact that intuitive biophysical reasons for such constraint are sometimes absent. Allostery may often provide the missing explanatory link. We use models of protein conformational change to identify allosteric residues by finding essential surface pockets and information-flow bottlenecks, and we develop a software tool that enables users to perform this analysis on their own proteins of interest. Though fundamentally 3D-structural in nature, our analysis is computationally fast, thereby allowing us to run it across the PDB and to evaluate general properties of predicted allosteric residues. We find that these tend to be conserved over diverse evolutionary time scales. Finally, we highlight examples of allosteric residues that help explain poorly understood disease-associated variants.
Keywords: Allosteric Site; Animals; Conserved Sequence; Humans; Proteome; Sequence Analysis, Protein; Software

IFT52 mutations destabilize anterograde complex assembly, disrupt ciliogenesis and result in short rib polydactyly syndrome. - Zhang, Wenjuan; Taylor, S Paige; Nevarez, Lisette; Lachman, Ralph S; Nickerson, Deborah A; Bamshad, Michael; Krakow, Deborah; Cohn, Daniel H (Hum Mol Genet, 2016)
The short-rib polydactyly syndromes (SRPS) encompass a radiographically and genetically heterogeneous group of skeletal ciliopathies that are characterized by a long narrow chest, short extremities, and variable occurrence of polydactyly. Radiographic abnormalities include undermineralization of the calvarium, shortened and bowed appendicular bones, trident shaped acetabula and polydactyly. In a case of SRPS we identified compound heterozygosity for mutations in IFT52, which encodes a component of the anterograde intraflagellar transport complex. The IFT52 mutant cells synthesized a significantly reduced amount of IFT52 protein, leading to reduced synthesis of IFT74, IFT81, IFT88 and ARL13B, other key anterograde complex members. Ciliogenesis was also disrupted in the mutant cells, with a 60% reduction in the presence of cilia on mutant cells and loss of cilia length regulation for the cells with cilia. These data demonstrate that IFT52 is essential for anterograde complex integrity and for the biosynthesis and maintenance of cilia. The data identify a new locus for SRPS and show that IFT52 mutations result in a ciliopathy with primary effects on the skeleton.
Keywords: Carrier Proteins; Cilia; Ciliopathies; Cytoskeletal Proteins; Flagella; Humans; Intracellular Signaling Peptides and Proteins; Multiprotein Complexes; Muscle Proteins; Mutation; Short Rib-Polydactyly Syndrome; Skeleton; Tumor Suppressor Proteins

Impaired Amino Acid Transport at the Blood Brain Barrier Is a Cause of Autism Spectrum Disorder. - Tărlungeanu, Dora C; Deliu, Elena; Dotter, Christoph P; Kara, Majdi; Janiesch, Philipp Christoph; Scalise, Mariafrancesca; Galluccio, Michele; Tesulov, Mateja; Morelli, Emanuela; Sonmez, Fatma Mujgan; Bilguvar, Kaya; Ohgaki, Ryuichi; et al. (Cell, 2016)
Autism spectrum disorders (ASD) are a group of genetic disorders often overlapping with other neurological conditions. We previously described abnormalities in the branched-chain amino acid (BCAA) catabolic pathway as a cause of ASD. Here, we show that the solute carrier transporter 7a5 (SLC7A5), a large neutral amino acid transporter localized at the blood brain barrier (BBB), has an essential role in maintaining normal levels of brain BCAAs. In mice, deletion of Slc7a5 from the endothelial cells of the BBB leads to atypical brain amino acid profile, abnormal mRNA translation, and severe neurological abnormalities. Furthermore, we identified several patients with autistic traits and motor delay carrying deleterious homozygous mutations in the SLC7A5 gene. Finally, we demonstrate that BCAA intracerebroventricular administration ameliorates abnormal behaviors in adult mutant mice. Our data elucidate a neurological syndrome defined by SLC7A5 mutations and support an essential role for the BCAA in human brain function.
Keywords: Amino Acids; Animals; Autism Spectrum Disorder; Blood-Brain Barrier; Brain; Female; Humans; Infant; Infant, Newborn; Large Neutral Amino Acid-Transporter 1; Male; Mice; Mice, Knockout; Mutation; Pedigree; Protein Biosynthesis; Receptor, TIE-2

An inactivating mutation in intestinal cell kinase, ICK, impairs hedgehog signalling and causes short rib-polydactyly syndrome. - Paige Taylor, S; Kunova Bosakova, Michaela; Varecha, Miroslav; Balek, Lukas; Barta, Tomas; Trantirek, Lukas; Jelinkova, Iva; Duran, Ivan; Vesela, Iva; Forlenza, Kimberly N; Martin, Jorge H; Hampl, Ales; et al. (Hum Mol Genet, 2016)
The short rib polydactyly syndromes (SRPS) are a group of recessively inherited, perinatal-lethal skeletal disorders primarily characterized by short ribs, shortened long bones, varying types of polydactyly and concomitant visceral abnormalities. Mutations in several genes affecting cilia function cause SRPS, revealing a role for cilia function in skeletal development. To identify additional SRPS genes and discover novel ciliary molecules required for normal skeletogenesis, we performed exome sequencing in a cohort of patients and identified homozygosity for a missense mutation, p.E80K, in Intestinal Cell Kinase, ICK, in one SRPS family. The p.E80K mutation abolished serine/threonine kinase activity, resulting in altered ICK subcellular and ciliary localization, increased cilia length, aberrant cartilage growth plate structure, defective Hedgehog and altered ERK signalling. These data identify ICK as an SRPS-associated gene and reveal that abnormalities in signalling pathways contribute to defective skeletogenesis.
Keywords: Abnormalities, Multiple; Cilia; Exome; Female; Hedgehog Proteins; Humans; Infant; MAP Kinase Signaling System; Pedigree; Pregnancy; Protein-Serine-Threonine Kinases; Sequence Analysis, DNA; Short Rib-Polydactyly Syndrome; Signal Transduction; Skeleton

Increasing Generality and Power of Rare-Variant Tests by Utilizing Extended Pedigrees. - Sul, Jae Hoon; Cade, Brian E; Cho, Michael H; Qiao, Dandi; Silverman, Edwin K; Redline, Susan; Sunyaev, Shamil (Am J Hum Genet, 2016)
Recently, multiple studies have performed whole-exome or whole-genome sequencing to identify groups of rare variants associated with complex traits and diseases. They have primarily utilized case-control study designs that often require thousands of individuals to reach acceptable statistical power. Family-based studies can be more powerful because a rare variant can be enriched in an extended pedigree and segregate with the phenotype. Although many methods have been proposed for using family data to discover rare variants involved in a disease, a majority of them focus on a specific pedigree structure and are designed to analyze either binary or continuously measured outcomes. In this article, we propose RareIBD, a general and powerful approach to identifying rare variants involved in disease susceptibility. Our method can be applied to large extended families of arbitrary structure, including pedigrees with only affected individuals. The method accommodates both binary and quantitative traits. A series of simulation experiments suggest that RareIBD is a powerful test that outperforms existing approaches. In addition, our method accounts for individuals in top generations, which are not usually genotyped in extended families. In contrast to available statistical tests, RareIBD generates accurate p values even when genetic data from these individuals are missing. We applied RareIBD, as well as other methods, to two extended family datasets generated by different genotyping technologies and representing different ethnicities. The analysis of real data confirmed that RareIBD is the only method that properly controls type I error.
Keywords: Datasets as Topic; Ethnic Groups; Family; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Male; Models, Genetic; Pedigree; Phenotype; Research Design

Keratoacanthoma Shares Driver Mutations with Cutaneous Squamous Cell Carcinoma. - Lim, Young H; Fisher, Jonathan M; Bosenberg, Marcus W; Choate, Keith A; Ko, Christine J (J Invest Dermatol, 2016)
Keywords: Aged; Aged, 80 and over; Biomarkers, Tumor; Biopsy; Carcinoma, Squamous Cell; Cohort Studies; Diagnosis, Differential; Exome; Female; Humans; Keratoacanthoma; Loss of Heterozygosity; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Skin; Skin Neoplasms; Whole Exome Sequencing

KIF5A mutations cause an infantile onset phenotype including severe myoclonus with evidence of mitochondrial dysfunction. - Duis, Jessica; Dean, Shannon; Applegate, Carolyn; Harper, Amy; Xiao, Rui; He, Weimin; Dollar, James D; Sun, Lisa R; Waberski, Marta Biderman; Crawford, Thomas O; Hamosh, Ada; Stafstrom, Carl E (Ann Neurol, 2016)
Missense mutations in kinesin family member 5A (KIF5A) cause spastic paraplegia 10. We report on 2 patients with de novo stop-loss frameshift variants in KIF5A resulting in a novel phenotype that includes severe infantile onset myoclonus, hypotonia, optic nerve abnormalities, dysphagia, apnea, and early developmental arrest. We propose that alteration and elongation of the carboxy-terminus of the protein has a dominant-negative effect, causing mitochondrial dysfunction in the setting of an abnormal kinesin "motor." These results highlight the role of expanded testing and whole-exome sequencing in critically ill infants and emphasize the importance of accurate test interpretation. Ann Neurol 2016;80:633-637.
Keywords: Apnea; Child, Preschool; Deglutition Disorders; Developmental Disabilities; Fatal Outcome; Female; Frameshift Mutation; Humans; Infant; Kinesins; Male; Mitochondrial Diseases; Muscle Hypotonia; Mutation; Myoclonus; Optic Nerve

Localized structural frustration for evaluating the impact of sequence variants. - Kumar, Sushant; Clarke, Declan; Gerstein, Mark (Nucleic Acids Res, 2016)
Population-scale sequencing is increasingly uncovering large numbers of rare single-nucleotide variants (SNVs) in coding regions of the genome. The rarity of these variants makes it challenging to evaluate their deleteriousness with conventional phenotype-genotype associations. Protein structures provide a way of addressing this challenge. Previous efforts have focused on globally quantifying the impact of SNVs on protein stability. However, local perturbations may severely impact protein functionality without strongly disrupting global stability (e.g. in relation to catalysis or allostery). Here, we describe a workflow in which localized frustration, quantifying unfavorable local interactions, is employed as a metric to investigate such effects. Using this workflow on the Protein Databank, we find that frustration produces many immediately intuitive results: for instance, disease-related SNVs create stronger changes in localized frustration than non-disease related variants, and rare SNVs tend to disrupt local interactions to a larger extent than common variants. Less obviously, we observe that somatic SNVs associated with oncogenes and tumor suppressor genes (TSGs) induce very different changes in frustration. In particular, those associated with TSGs change the frustration more in the core than the surface (by introducing loss-of-function events), whereas those associated with oncogenes manifest the opposite pattern, creating gain-of-function events.
Keywords: Computational Biology; Databases, Protein; Evolution, Molecular; Genes, Tumor Suppressor; Genetic Variation; Humans; Neoplasms; Oncogenes; Polymorphism, Single Nucleotide; Proteins; Workflow

Loss of B Cells in Patients with Heterozygous Mutations in IKAROS. - Kuehn, H S; Boisson, B; Cunningham-Rundles, C; Reichenbach, J; Stray-Pedersen, A; Gelfand, E W; Maffucci, P; Pierce, K R; Abbott, J K; Voelkerding, K V; South, S T; Augustine, N H; et al. (N Engl J Med, 2016)
BACKGROUND: Common variable immunodeficiency (CVID) is characterized by late-onset hypogammaglobulinemia in the absence of predisposing factors. The genetic cause is unknown in the majority of cases, and less than 10% of patients have a family history of the disease. Most patients have normal numbers of B cells but lack plasma cells. METHODS: We used whole-exome sequencing and array-based comparative genomic hybridization to evaluate a subset of patients with CVID and low B-cell numbers. Mutant proteins were analyzed for DNA binding with the use of an electrophoretic mobility-shift assay (EMSA) and confocal microscopy. Flow cytometry was used to analyze peripheral-blood lymphocytes and bone marrow aspirates. RESULTS: Six different heterozygous mutations in IKZF1, the gene encoding the transcription factor IKAROS, were identified in 29 persons from six families. In two families, the mutation was a de novo event in the proband. All the mutations, four amino acid substitutions, an intragenic deletion, and a 4.7-Mb multigene deletion involved the DNA-binding domain of IKAROS. The proteins bearing missense mutations failed to bind target DNA sequences on EMSA and confocal microscopy; however, they did not inhibit the binding of wild-type IKAROS. Studies in family members showed progressive loss of B cells and serum immunoglobulins. Bone marrow aspirates in two patients had markedly decreased early B-cell precursors, but plasma cells were present. Acute lymphoblastic leukemia developed in 2 of the 29 patients. CONCLUSIONS: Heterozygous mutations in the transcription factor IKAROS caused an autosomal dominant form of CVID that is associated with a striking decrease in B-cell numbers. (Funded by the National Institutes of Health and others.).
Keywords: Adolescent; Adult; Antigens, CD; B-Lymphocytes; Bone Marrow; Bone Marrow Examination; Child; Child, Preschool; Chromosomes, Human, Pair 7; Common Variable Immunodeficiency; Exome; Female; Heterozygote; Humans; Ikaros Transcription Factor; Immunoglobulin G; Lymphocyte Count; Male; Mutation; Pedigree; Sequence Analysis, DNA

Loss of carbonic anhydrase XII function in individuals with elevated sweat chloride concentration and pulmonary airway disease. - Lee, Melissa; Vecchio-Pagán, Briana; Sharma, Neeraj; Waheed, Abdul; Li, Xiaopeng; Raraigh, Karen S; Robbins, Sarah; Han, Sangwoo T; Franca, Arianna L; Pellicore, Matthew J; Evans, Taylor A; Arcara, Kristin M; et al. (Hum Mol Genet, 2016)
Elevated sweat chloride levels, failure to thrive (FTT), and lung disease are characteristic features of cystic fibrosis (CF, OMIM #219700). Here we describe variants in CA12 encoding carbonic anhydrase XII in two pedigrees exhibiting CF-like phenotypes. Exome sequencing of a white American adult diagnosed with CF due to elevated sweat chloride, recurrent hyponatremia, infantile FTT and lung disease identified deleterious variants in each CA12 gene: c.908-1 G>A in a splice acceptor and a novel frameshift insertion c.859_860insACCT. In an unrelated consanguineous Omani family, two children with elevated sweat chloride, infantile FTT, and recurrent hyponatremia were homozygous for a novel missense variant (p.His121Gln). Deleterious CFTR variants were absent in both pedigrees. CA XII protein was localized apically in human bronchiolar epithelia and basolaterally in the reabsorptive duct of human sweat glands. Respiratory epithelial cell RNA from the adult proband revealed only aberrant CA12 transcripts and in vitro analysis showed greatly reduced CA XII protein. Studies of ion transport across respiratory epithelial cells in vivo and in culture revealed intact CFTR-mediated chloride transport in the adult proband. CA XII protein bearing either p.His121Gln or a previously identified p.Glu143Lys missense variant localized to the basolateral membranes of polarized Madin-Darby canine kidney (MDCK) cells, but enzyme activity was severely diminished when assayed at physiologic concentrations of extracellular chloride. Our findings indicate that loss of CA XII function should be considered in individuals without CFTR mutations who exhibit CF-like features in the sweat gland and lung.
Keywords: Adolescent; Adult; Animals; Carbonic Anhydrases; Child; Child, Preschool; Chlorides; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Dogs; Female; Gene Expression Regulation, Enzymologic; Homozygote; Humans; Lung; Lung Diseases; Madin Darby Canine Kidney Cells; Male; Mutation; Pedigree; Phenotype; Sweat

Loss-of-Function Mutations in FRRS1L Lead to an Epileptic-Dyskinetic Encephalopathy. - Madeo, Marianna; Stewart, Michelle; Sun, Yuyang; Sahir, Nadia; Wiethoff, Sarah; Chandrasekar, Indra; Yarrow, Anna; Rosenfeld, Jill A; Yang, Yaping; Cordeiro, Dawn; McCormick, Elizabeth M; Muraresku, Colleen C; et al. (Am J Hum Genet, 2016)
Glutamatergic neurotransmission governs excitatory signaling in the mammalian brain, and abnormalities of glutamate signaling have been shown to contribute to both epilepsy and hyperkinetic movement disorders. The etiology of many severe childhood movement disorders and epilepsies remains uncharacterized. We describe a neurological disorder with epilepsy and prominent choreoathetosis caused by biallelic pathogenic variants in FRRS1L, which encodes an AMPA receptor outer-core protein. Loss of FRRS1L function attenuates AMPA-mediated currents, implicating chronic abnormalities of glutamatergic neurotransmission in this monogenic neurological disease of childhood.
Keywords: alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid; Brain Diseases; Electrophysiology; Epilepsy; Female; Humans; Hyperkinesis; Infant; Male; Membrane Proteins; Mutation; Nerve Tissue Proteins; Pedigree; Synaptic Transmission

Loss-of-function variants influence the human serum metabolome. - Yu, Bing; Li, Alexander H; Metcalf, Ginger A; Muzny, Donna M; Morrison, Alanna C; White, Simon; Mosley, Thomas H; Gibbs, Richard A; Boerwinkle, Eric (Sci Adv, 2016)
The metabolome is a collection of small molecules resulting from multiple cellular and biological processes that can act as biomarkers of disease, and African-Americans exhibit high levels of genetic diversity. Exome sequencing of a sample of deeply phenotyped African-Americans allowed us to analyze the effects of annotated loss-of-function (LoF) mutations on 308 serum metabolites measured by untargeted liquid and gas chromatography coupled with mass spectrometry. In an independent sample, we identified and replicated four genes harboring six LoF mutations that significantly affected five metabolites. These sites were related to a 19 to 45% difference in geometric mean metabolite levels, with an average effect size of 25%. We show that some of the affected metabolites are risk predictors or diagnostic biomarkers of disease and, using the principle of Mendelian randomization, are in the causal pathway of disease. For example, LoF mutations in SLCO1B1 elevate the levels of hexadecanedioate, a fatty acid significantly associated with increased blood pressure levels and risk of incident heart failure in both African-Americans and an independent sample of European-Americans. We show that SLCO1B1 LoF mutations significantly increase the risk of incident heart failure, thus implicating the metabolite in the causal pathway of disease. These results reveal new avenues into gene function and the understanding of disease etiology by integrating -omic technologies into a deeply phenotyped population study.
Keywords: Aged; Biomarkers; Black or African American; Exome; Female; Genetic Variation; Heart Failure; High-Throughput Nucleotide Sequencing; Humans; Hypertension; Liver-Specific Organic Anion Transporter 1; Male; Metabolome; Middle Aged; Mutation; Risk Factors; White People

Low-level APC mutational mosaicism is the underlying cause in a substantial fraction of unexplained colorectal adenomatous polyposis cases. - Spier, Isabel; Drichel, Dmitriy; Kerick, Martin; Kirfel, Jutta; Horpaopan, Sukanya; Laner, Andreas; Holzapfel, Stefanie; Peters, Sophia; Adam, Ronja; Zhao, Bixiao; Becker, Tim; Lifton, Richard P; et al. (J Med Genet, 2016)
BACKGROUND: In 30-50% of patients with colorectal adenomatous polyposis, no germline mutation in the known genes APC, causing familial adenomatous polyposis, MUTYH, causing MUTYH-associated polyposis, or POLE or POLD1, causing polymerase-proofreading-associated polyposis can be identified, although a hereditary aetiology is likely. This study aimed to explore the impact of APC mutational mosaicism in unexplained polyposis. METHODS: To comprehensively screen for somatic low-level APC mosaicism, high-coverage next-generation sequencing of the APC gene was performed using DNA from leucocytes and a total of 53 colorectal tumours from 20 unrelated patients with unexplained sporadic adenomatous polyposis. APC mosaicism was assumed if the same loss-of-function APC mutation was present in ≥ 2 anatomically separated colorectal adenomas/carcinomas per patient. All mutations were validated using diverse methods. RESULTS: In 25% (5/20) of patients, somatic mosaicism of a pathogenic APC mutation was identified as underlying cause of the disease. In 2/5 cases, the mosaic level in leucocyte DNA was slightly below the sensitivity threshold of Sanger sequencing; while in 3/5 cases, the allelic fraction was either very low (0.1-1%) or no mutations were detectable. The majority of mosaic mutations were located outside the somatic mutation cluster region of the gene. CONCLUSIONS: The present data indicate a high prevalence of pathogenic mosaic APC mutations below the detection thresholds of routine diagnostics in adenomatous polyposis, even if high-coverage sequencing of leucocyte DNA alone is taken into account. This has important implications for both routine work-up and strategies to identify new causative genes in this patient group.
Keywords: Adenomatous Polyposis Coli; Adolescent; Adult; Colorectal Neoplasms; Genes, APC; High-Throughput Nucleotide Sequencing; Humans; Middle Aged; Mutation; Mutation Rate

LOX Mutations Predispose to Thoracic Aortic Aneurysms and Dissections. - Guo, Dong-Chuan; Regalado, Ellen S; Gong, Limin; Duan, Xueyan; Santos-Cortez, Regie Lyn P; Arnaud, Pauline; Ren, Zhao; Cai, Bo; Hostetler, Ellen M; Moran, Rocio; Liang, David; Estrera, Anthony; et al. (Circ Res, 2016)
RATIONALE: Mutations in several genes have been identified that are responsible for 25% of families with familial thoracic aortic aneurysms and dissections. However, the causative gene remains unknown in 75% of families. OBJECTIVES: To identify the causative mutation in families with autosomal dominant inheritance of thoracic aortic aneurysms and dissections. METHODS AND RESULTS: Exome sequencing was used to identify the mutation responsible for a large family with thoracic aortic aneurysms and dissections. A heterozygous rare variant, c.839G>T (p.Ser280Arg), was identified in LOX, encoding a lysyl oxidase, that segregated with disease in the family. Sanger and exome sequencing was used to investigate mutations in LOX in an additional 410 probands from unrelated families. Additional LOX rare variants that segregated with disease in families were identified, including c.125G>A (p.Trp42*), c.604G>T (p.Gly202*), c.743C>T (p.Thr248Ile), c.800A>C (p.Gln267Pro), and c.1044T>A (p.Ser348Arg). The altered amino acids cause haploinsufficiency for LOX or are located at a highly conserved LOX catalytic domain, which is relatively invariant in the population. Expression of the LOX variants p.Ser280Arg and p.Ser348Arg resulted in significantly lower lysyl oxidase activity when compared with the wild-type protein. Individuals with LOX variants had fusiform enlargement of the root and ascending thoracic aorta, leading to ascending aortic dissections. CONCLUSIONS: These data, along with previous studies showing that the deficiency of LOX in mice or inhibition of lysyl oxidases in turkeys and rats causes aortic dissections, support the conclusion that rare genetic variants in LOX predispose to thoracic aortic disease.
Keywords: Adult; Aged; Amino Acid Sequence; Aneurysm, Dissecting; Aortic Aneurysm, Thoracic; Female; Genetic Variation; Humans; Male; Middle Aged; Molecular Sequence Data; Mutation; Pedigree; Protein-Lysine 6-Oxidase

Mechanisms for the Generation of Two Quadruplications Associated with Split-Hand Malformation. - Gu, Shen; Posey, Jennifer E; Yuan, Bo; Carvalho, Claudia M B; Luk, H M; Erikson, Kelly; Lo, Ivan F M; Leung, Gordon K C; Pickering, Curtis R; Chung, Brian H Y; Lupski, James R (Hum Mutat, 2016)
Germline copy-number variants (CNVs) involving quadruplications are rare and the mechanisms generating them are largely unknown. Previously, we reported a 20-week gestation fetus with split-hand malformation; clinical microarray detected two maternally inherited triplications separated by a copy-number neutral region at 17p13.3, involving BHLHA9 and part of YWHAE. Here, we describe an 18-month-old male sibling of the previously described fetus with split-hand malformation. Custom high-density microarray and digital droplet PCR revealed the copy-number gains were actually quadruplications in the mother, the fetus, and her later born son. This quadruplication-normal-quadruplication pattern was shown to be expanded from the triplication-normal-triplication CNV at the same loci in the maternal grandmother. We mapped two breakpoint junctions and demonstrated that both are mediated by Alu repetitive elements and identical in these four individuals. We propose a three-step process combining Alu-mediated replicative-repair-based mechanism(s) and intergenerational, intrachromosomal nonallelic homologous recombination to generate the quadruplications in this family.
Keywords: 14-3-3 Proteins; Adult; Aged; Alu Elements; Base Sequence; Basic Helix-Loop-Helix Transcription Factors; Chromosome Duplication; Chromosomes, Human, Pair 17; DNA Copy Number Variations; Female; Genetic Loci; Genome, Human; Hand Deformities, Congenital; Humans; Infant; Male; Molecular Sequence Data; Pedigree; Sequence Alignment; Sequence Analysis, DNA

Mechanisms underlying structural variant formation in genomic disorders. - Carvalho, Claudia M B; Lupski, James R (Nat Rev Genet, 2016)
With the recent burst of technological developments in genomics, and the clinical implementation of genome-wide assays, our understanding of the molecular basis of genomic disorders, specifically the contribution of structural variation to disease burden, is evolving quickly. Ongoing studies have revealed a ubiquitous role for genome architecture in the formation of structural variants at a given locus, both in DNA recombination-based processes and in replication-based processes. These reports showcase the influence of repeat sequences on genomic stability and structural variant complexity and also highlight the tremendous plasticity and dynamic nature of our genome in evolution, health and disease susceptibility.
Keywords: Gene Rearrangement; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genomic Instability; Homologous Recombination; Humans; Models, Genetic; Mutation; Repetitive Sequences, Nucleic Acid

MECR Mutations Cause Childhood-Onset Dystonia and Optic Atrophy, a Mitochondrial Fatty Acid Synthesis Disorder. - Heimer, Gali; Kerätär, Juha M; Riley, Lisa G; Balasubramaniam, Shanti; Eyal, Eran; Pietikäinen, Laura P; Hiltunen, J Kalervo; Marek-Yagel, Dina; Hamada, Jeffrey; Gregory, Allison; Rogers, Caleb; Hogarth, Penelope; et al. (Am J Hum Genet, 2016)
Mitochondrial fatty acid synthesis (mtFAS) is an evolutionarily conserved pathway essential for the function of the respiratory chain and several mitochondrial enzyme complexes. We report here a unique neurometabolic human disorder caused by defective mtFAS. Seven individuals from five unrelated families presented with childhood-onset dystonia, optic atrophy, and basal ganglia signal abnormalities on MRI. All affected individuals were found to harbor recessive mutations in MECR encoding the mitochondrial trans-2-enoyl-coenzyme A-reductase involved in human mtFAS. All six mutations are extremely rare in the general population, segregate with the disease in the families, and are predicted to be deleterious. The nonsense c.855T>G (p.Tyr285), c.247_250del (p.Asn83Hisfs4), and splice site c.830+2_830+3insT mutations lead to C-terminal truncation variants of MECR. The missense c.695G>A (p.Gly232Glu), c.854A>G (p.Tyr285Cys), and c.772C>T (p.Arg258Trp) mutations involve conserved amino acid residues, are located within the cofactor binding domain, and are predicted by structural analysis to have a destabilizing effect. Yeast modeling and complementation studies validated the pathogenicity of the MECR mutations. Fibroblast cell lines from affected individuals displayed reduced levels of both MECR and lipoylated proteins as well as defective respiration. These results suggest that mutations in MECR cause a distinct human disorder of the mtFAS pathway. The observation of decreased lipoylation raises the possibility of a potential therapeutic strategy.
Keywords: Basal Ganglia; Cells, Cultured; Child; Child, Preschool; Dystonic Disorders; Fatty Acids; Female; Fibroblasts; Genetic Complementation Test; Humans; Infant; Male; Mitochondria; Mitochondrial Diseases; Models, Molecular; Mutation; Mutation, Missense; Optic Atrophy; Oxidoreductases Acting on CH-CH Group Donors; Pedigree; RNA Splice Sites; Saccharomyces cerevisiae

MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. - Eldomery, Mohammad K; Akdemir, Zeynep C; Vögtle, F-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill A; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay C; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini N; et al. (Genome Med, 2016)
BACKGROUND: Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. METHODS: Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organism Saccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. RESULTS: Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) in MIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includes MIPEP. All amino acids affected in the patients' missense variants are highly conserved from yeast to human and therefore S. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. CONCLUSIONS: Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.
Keywords: Adult; Amino Acid Sequence; Female; Genes, Recessive; Heart Defects, Congenital; Humans; Infant; Infant, Newborn; Male; Metalloendopeptidases; Muscle Hypotonia; Pedigree; Phenotype; Sequence Homology, Amino Acid; Sudden Infant Death; Syndrome

Mitral regurgitation as a phenotypic manifestation of nonphotosensitive trichothiodystrophy due to a splice variant in MPLKIP. - Shah, Khadim; Ali, Raja Hussain; Ansar, Muhammad; Lee, Kwanghyuk; Chishti, Muhammad Salman; Abbe, Izoduwa; Li, Biao; Smith, Joshua D; Nickerson, Deborah A; Shendure, Jay; Coucke, Paul J; Steyaert, Wouter; et al. (BMC Med Genet, 2016)
BACKGROUND: Nonphotosensitive trichothiodystrophy (TTDN) is a rare autosomal recessive disorder of neuroectodermal origin. The condition is marked by hair abnormalities, intellectual impairment, nail dystrophies and susceptibility to infections but with no UV sensitivity. METHODS: We identified three consanguineous Pakistani families with varied TTDN features and used homozygosity mapping, linkage analysis, and Sanger and exome sequencing in order to identify pathogenic variants. Haplotype analysis was performed and haplotype age estimated. A splicing assay was used to validate the effect of the MPLKIP splice variant on expression. RESULTS: Affected individuals from all families exhibit several TTDN features along with a heart-specific feature, i.e. mitral regurgitation. Exome sequencing in the probands from families ED168 and ED241 identified a homozygous splice mutation c.339 + 1G > A within MPLKIP. The same splice variant co-segregates with TTDN in a third family ED210. The MPLKIP splice variant was not found in public databases, e.g. the Exome Aggregation Consortium, and in unrelated Pakistani controls. Functional analysis of the splice variant confirmed intron retention, which leads to protein truncation and loss of a phosphorylation site. Haplotype analysis identified a 585.1-kb haplotype which includes the MPLKIP variant, supporting the existence of a founder haplotype that is estimated to be 25,900 years old. CONCLUSION: This study extends the allelic and phenotypic spectra of MPLKIP-related TTDN, to include a splice variant that causes cardiomyopathy as part of the TTDN phenotype.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Alleles; Asian Continental Ancestry Group; Child; Cloning, Molecular; Exome; Female; Genetic Linkage; Haplotypes; HEK293 Cells; Homozygote; Humans; Introns; Male; Mitral Valve Insufficiency; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; RNA Splicing; Sequence Analysis, DNA; Trichothiodystrophy Syndromes; Young Adult

Molecular diagnostic experience of whole-exome sequencing in adult patients. - Posey, Jennifer E; Rosenfeld, Jill A; James, Regis A; Bainbridge, Matthew; Niu, Zhiyv; Wang, Xia; Dhar, Shweta; Wiszniewski, Wojciech; Akdemir, Zeynep H C; Gambin, Tomasz; Xia, Fan; Person, Richard E; et al. (Genet Med, 2016)
PURPOSE: Whole-exome sequencing (WES) is increasingly used as a diagnostic tool in medicine, but prior reports focus on predominantly pediatric cohorts with neurologic or developmental disorders. We describe the diagnostic yield and characteristics of WES in adults. METHODS: We performed a retrospective analysis of consecutive WES reports for adults from a diagnostic laboratory. Phenotype composition was determined using Human Phenotype Ontology terms. RESULTS: Molecular diagnoses were reported for 17.5% (85/486) of adults, which is lower than that for a primarily pediatric population (25.2%; P = 0.0003); the diagnostic rate was higher (23.9%) for those 18-30 years of age compared to patients older than 30 years (10.4%; P = 0.0001). Dual Mendelian diagnoses contributed to 7% of diagnoses, revealing blended phenotypes. Diagnoses were more frequent among individuals with abnormalities of the nervous system, skeletal system, head/neck, and growth. Diagnostic rate was independent of family history information, and de novo mutations contributed to 61.4% of autosomal dominant diagnoses. CONCLUSION: Early WES experience in adults demonstrates molecular diagnoses in a substantial proportion of patients, informing clinical management, recurrence risk, and recommendations for relatives. A positive family history was not predictive, consistent with molecular diagnoses often revealed by de novo events, informing the Mendelian basis of genetic disease in adults.Genet Med 18 7, 678-685.
Keywords: Adult; Exome; Female; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Pathology, Molecular

Molecular etiology of arthrogryposis in multiple families of mostly Turkish origin. - Bayram, Yavuz; Karaca, Ender; Coban Akdemir, Zeynep; Yilmaz, Elif Ozdamar; Tayfun, Gulsen Akay; Aydin, Hatip; Torun, Deniz; Bozdogan, Sevcan Tug; Gezdirici, Alper; Isikay, Sedat; Atik, Mehmed M; Gambin, Tomasz; et al. (J Clin Invest, 2016)
BACKGROUND: Arthrogryposis, defined as congenital joint contractures in 2 or more body areas, is a clinical sign rather than a specific disease diagnosis. To date, more than 400 different disorders have been described that present with arthrogryposis, and variants of more than 220 genes have been associated with these disorders; however, the underlying molecular etiology remains unknown in the considerable majority of these cases. METHODS: We performed whole exome sequencing (WES) of 52 patients with clinical presentation of arthrogryposis from 48 different families. RESULTS: Affected individuals from 17 families (35.4%) had variants in known arthrogryposis-associated genes, including homozygous variants of cholinergic γ nicotinic receptor (CHRNG, 6 subjects) and endothelin converting enzyme-like 1 (ECEL1, 4 subjects). Deleterious variants in candidate arthrogryposis-causing genes (fibrillin 3 [FBN3], myosin IXA [MYO9A], and pleckstrin and Sec7 domain containing 3 [PSD3]) were identified in 3 families (6.2%). Moreover, in 8 families with a homozygous mutation in an arthrogryposis-associated gene, we identified a second locus with either a homozygous or compound heterozygous variant in a candidate gene (myosin binding protein C, fast type [MYBPC2] and vacuolar protein sorting 8 [VPS8], 2 families, 4.2%) or in another disease-associated genes (6 families, 12.5%), indicating a potential mutational burden contributing to disease expression. CONCLUSION: In 58.3% of families, the arthrogryposis manifestation could be explained by a molecular diagnosis; however, the molecular etiology in subjects from 20 families remained unsolved by WES. Only 5 of these 20 unrelated subjects had a clinical presentation consistent with amyoplasia; a phenotype not thought to be of genetic origin. Our results indicate that increased use of genome-wide technologies will provide opportunities to better understand genetic models for diseases and molecular mechanisms of genetically heterogeneous disorders, such as arthrogryposis. FUNDING: This work was supported in part by US National Human Genome Research Institute (NHGRI)/National Heart, Lung, and Blood Institute (NHLBI) grant U54HG006542 to the Baylor-Hopkins Center for Mendelian Genomics, and US National Institute of Neurological Disorders and Stroke (NINDS) grant R01NS058529 to J.R. Lupski.
Keywords: Arthrogryposis; Exome; Family; Female; Genome-Wide Association Study; Humans; Male; Turkey

Monoallelic and Biallelic Variants in EMC1 Identified in Individuals with Global Developmental Delay, Hypotonia, Scoliosis, and Cerebellar Atrophy. - Harel, Tamar; Yesil, Gözde; Bayram, Yavuz; Coban-Akdemir, Zeynep; Charng, Wu-Lin; Karaca, Ender; Al Asmari, Ali; Eldomery, Mohammad K; Hunter, Jill V; Jhangiani, Shalini N; Rosenfeld, Jill A; Pehlivan, Davut; et al. (Am J Hum Genet, 2016)
The paradigm of a single gene associated with one specific phenotype and mode of inheritance has been repeatedly challenged. Genotype-phenotype correlations can often be traced to different mutation types, localization of the variants in distinct protein domains, or the trigger of or escape from nonsense-mediated decay. Using whole-exome sequencing, we identified homozygous variants in EMC1 that segregated with a phenotype of developmental delay, hypotonia, scoliosis, and cerebellar atrophy in three families. In addition, a de novo heterozygous EMC1 variant was seen in an individual with a similar clinical and MRI imaging phenotype. EMC1 encodes a member of the endoplasmic reticulum (ER)-membrane protein complex (EMC), an evolutionarily conserved complex that has been proposed to have multiple roles in ER-associated degradation, ER-mitochondria tethering, and proper assembly of multi-pass transmembrane proteins. Perturbations of protein folding and organelle crosstalk have been implicated in neurodegenerative processes including cerebellar atrophy. We propose EMC1 as a gene in which either biallelic or monoallelic variants might lead to a syndrome including intellectual disability and preferential degeneration of the cerebellum.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Atrophy; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Female; Genetic Association Studies; Genetic Variation; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Muscle Hypotonia; Mutation; Pedigree; Protein Folding; Proteins; Scoliosis

Mosaic Activating Mutations in FGFR1 Cause Encephalocraniocutaneous Lipomatosis. - Bennett, James T; Tan, Tiong Yang; Alcantara, Diana; Tétrault, Martine; Timms, Andrew E; Jensen, Dana; Collins, Sarah; Nowaczyk, Malgorzata J M; Lindhurst, Marjorie J; Christensen, Katherine M; Braddock, Stephen R; Brandling-Bennett, Heather; et al. (Am J Hum Genet, 2016)
Encephalocraniocutaneous lipomatosis (ECCL) is a sporadic condition characterized by ocular, cutaneous, and central nervous system anomalies. Key clinical features include a well-demarcated hairless fatty nevus on the scalp, benign ocular tumors, and central nervous system lipomas. Seizures, spasticity, and intellectual disability can be present, although affected individuals without seizures and with normal intellect have also been reported. Given the patchy and asymmetric nature of the malformations, ECCL has been hypothesized to be due to a post-zygotic, mosaic mutation. Despite phenotypic overlap with several other disorders associated with mutations in the RAS-MAPK and PI3K-AKT pathways, the molecular etiology of ECCL remains unknown. Using exome sequencing of DNA from multiple affected tissues from five unrelated individuals with ECCL, we identified two mosaic mutations, c.1638C>A (p.Asn546Lys) and c.1966A>G (p.Lys656Glu) within the tyrosine kinase domain of FGFR1, in two affected individuals each. These two residues are the most commonly mutated residues in FGFR1 in human cancers and are associated primarily with CNS tumors. Targeted resequencing of FGFR1 in multiple tissues from an independent cohort of individuals with ECCL identified one additional individual with a c.1638C>A (p.Asn546Lys) mutation in FGFR1. Functional studies of ECCL fibroblast cell lines show increased levels of phosphorylated FGFRs and phosphorylated FRS2, a direct substrate of FGFR1, as well as constitutive activation of RAS-MAPK signaling. In addition to identifying the molecular etiology of ECCL, our results support the emerging overlap between mosaic developmental disorders and tumorigenesis.
Keywords: Adolescent; Cell Line, Tumor; Central Nervous System Neoplasms; Child, Preschool; Exome; Eye; Eye Diseases; Female; Humans; Infant; Lipomatosis; Male; Mutation; Mutation, Missense; Neurocutaneous Syndromes; Phosphatidylinositol 3-Kinases; Proto-Oncogene Proteins c-akt; Receptor, Fibroblast Growth Factor, Type 1; Seizures; Sequence Analysis, DNA

Multiallelic Positions in the Human Genome: Challenges for Genetic Analyses. - Campbell, Ian M; Gambin, Tomasz; Jhangiani, Shalini; Grove, Megan L; Veeraraghavan, Narayanan; Muzny, Donna M; Shaw, Chad A; Gibbs, Richard A; Boerwinkle, Eric; Yu, Fuli; Lupski, James R (Hum Mutat, 2016)
As the amount of human genomic sequence available from personal genomes and exomes has increased, so too has the observation of genomic positions having two or more alternative alleles, so-called multiallelic sites. For portions of the haploid genome that are present in more than one copy, including segmental duplications, variation at such multisite variant positions becomes even more complex. Despite the frequency of multiallelic variants, a number of commonly used resources and tools in genomic research and diagnostics do not support these multiallelic variants all together or require special modifications. Here, we explore the frequency of multiallelic sites in large samples with whole exome sequencing and discuss potential outcomes of failing to account for multiple variant alleles. We also briefly discuss some commonly utilized resources that fully support multiallelic sites.
Keywords: Alleles; Exome; Genome, Human; Humans

Mutational Spectrum of MYO15A and the Molecular Mechanisms of DFNB3 Human Deafness. - Rehman, Atteeq U; Bird, Jonathan E; Faridi, Rabia; Shahzad, Mohsin; Shah, Sujay; Lee, Kwanghyuk; Khan, Shaheen N; Imtiaz, Ayesha; Ahmed, Zubair M; Riazuddin, Saima; Santos-Cortez, Regie Lyn P; Ahmad, Wasim; et al. (Hum Mutat, 2016)
Deafness in humans is a common neurosensory disorder and is genetically heterogeneous. Across diverse ethnic groups, mutations of MYO15A at the DFNB3 locus appear to be the third or fourth most common cause of autosomal-recessive, nonsyndromic deafness. In 49 of the 67 exons of MYO15A, there are currently 192 recessive mutations identified, including 14 novel mutations reported here. These mutations are distributed uniformly across MYO15A with one enigmatic exception; the alternatively spliced giant exon 2, encoding 1,233 residues, has 17 truncating mutations but no convincing deafness-causing missense mutations. MYO15A encodes three distinct isoform classes, one of which is 395 kDa (3,530 residues), the largest member of the myosin superfamily of molecular motors. Studies of Myo15 mouse models that recapitulate DFNB3 revealed two different pathogenic mechanisms of hearing loss. In the inner ear, myosin 15 is necessary both for the development and the long-term maintenance of stereocilia, mechanosensory sound-transducing organelles that extend from the apical surface of hair cells. The goal of this Mutation Update is to provide a comprehensive review of mutations and functions of MYO15A.
Keywords: Alternative Splicing; Animals; Deafness; Disease Models, Animal; Ear, Inner; Exons; Gene Expression Regulation, Developmental; Humans; Mice; Mutation; Myosins; Stereocilia

Mutations in CEP120 cause Joubert syndrome as well as complex ciliopathy phenotypes. - Roosing, Susanne; Romani, Marta; Isrie, Mala; Rosti, Rasim Ozgur; Micalizzi, Alessia; Musaev, Damir; Mazza, Tommaso; Al-Gazali, Lihadh; Altunoglu, Umut; Boltshauser, Eugen; D'Arrigo, Stefano; De Keersmaecker, Bart; et al. (J Med Genet, 2016)
BACKGROUND: Ciliopathies are an extensive group of autosomal recessive or X-linked disorders with considerable genetic and clinical overlap, which collectively share multiple organ involvement and may result in lethal or viable phenotypes. In large numbers of cases the genetic defect remains yet to be determined. The aim of this study is to describe the mutational frequency and phenotypic spectrum of the CEP120 gene. METHODS: Exome sequencing was performed in 145 patients with Joubert syndrome (JS), including 15 children with oral-facial-digital syndrome type VI (OFDVI) and 21 Meckel syndrome (MKS) fetuses. Moreover, exome sequencing was performed in one fetus with tectocerebellar dysraphia with occipital encephalocele (TCDOE), molar tooth sign and additional skeletal abnormalities. As a parallel study, 346 probands with a phenotype consistent with JS or related ciliopathies underwent next-generation sequencing-based targeted sequencing of 120 previously described and candidate ciliopathy genes. RESULTS: We present six probands carrying nine distinct mutations (of which eight are novel) in the CEP120 gene, previously found mutated only in Jeune asphyxiating thoracic dystrophy (JATD). The CEP120-associated phenotype ranges from mild classical JS in four patients to more severe conditions in two fetuses, with overlapping features of distinct ciliopathies that include TCDOE, MKS, JATD and OFD syndromes. No obvious correlation is evident between the type or location of identified mutations and the ciliopathy phenotype. CONCLUSION: Our findings broaden the spectrum of phenotypes caused by CEP120 mutations that account for nearly 1% of patients with JS as well as for more complex ciliopathy phenotypes. The lack of clear genotype-phenotype correlation highlights the relevance of comprehensive genetic analyses in the diagnostics of ciliopathies.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Cell Cycle Proteins; Cerebellar Diseases; Cerebellum; Child; Ciliopathies; Encephalocele; Eye Abnormalities; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Humans; Kidney Diseases, Cystic; Male; Mutation; Mutation Rate; Orofaciodigital Syndromes; Pedigree; Phenotype; Retina; Sequence Alignment

Mutations in DCDC2 (doublecortin domain containing protein 2) in neonatal sclerosing cholangitis. - Grammatikopoulos, Tassos; Sambrotta, Melissa; Strautnieks, Sandra; Foskett, Pierre; Knisely, A S; Wagner, Bart; Deheragoda, Maesha; Starling, Chris; Mieli-Vergani, Giorgina; Smith, Joshua; Bull, Laura; Thompson, Richard J (J Hepatol, 2016)
BACKGROUND & AIMS: Neonatal sclerosing cholangitis (NSC) is a severe neonatal-onset cholangiopathy commonly leading to liver transplantation (LT) for end-stage liver disease in childhood. Liver biopsy findings histopathologically resemble those in biliary atresia (BA); however, in NSC extrahepatic bile ducts are patent, whilst in BA their lumina are obliterated. NSC is commonly seen in consanguineous kindreds, suggesting autosomal recessive inheritance. METHODS: From 29 NSC patients (24 families) identified, DNA was available in 24 (21 families). Thirteen (7 male) patients (12 families) of consanguineous parentage were selected for whole exome sequencing. Sequence variants were filtered for homozygosity, pathogenicity, minor allele frequency, quality score, and encoded protein expression pattern. RESULTS: Four of 13 patients were homozygous and two were compound heterozygous for mutations in the doublecortin domain containing 2 gene (DCDC2), which encodes DCDC2 protein and is expressed in cholangiocyte cilia. Another 11 patients were sequenced: one (with one sibling pair) was compound heterozygous for DCDC2 mutations. All mutations were protein-truncating. In available liver tissue from patients with DCDC2 mutations, immunostaining for human DCDC2 and the ciliary protein acetylated alpha-tubulin (ACALT) showed no expression (n=6) and transmission electron microscopy found that cholangiocytes lacked primary cilia (n=5). DCDC2 and ACALT were expressed in NSC patients without DCDC2 mutations (n=22). Of the patients carrying DCDC2 mutations, one died awaiting LT; five came to LT, of whom one died 2years later. The other 4 are well. CONCLUSION: Among 24 NSC patients with available DNA, 7 had mutations in DCDC2 (6 of 19 families). NSC patients in substantial proportion harbour mutations in DCDC2. Their disease represents a novel liver-based ciliopathy. LAY SUMMARY: Neonatal sclerosing cholangitis (NSC) is a rare genetic form of liver disease presenting in infancy. Through next generation sequencing we identified mutations in the gene encoding for doublecortin domain containing 2 (DCDC2) protein in a group of NSC children. DCDC2 is a signalling and structural protein found in primary cilia of cholangiocytes. Cholangiocytes are the cells forming the biliary system which is the draining system of the liver.
Keywords: Cholangitis, Sclerosing; Female; High-Throughput Nucleotide Sequencing; Humans; Infant, Newborn; Male; Microtubule-Associated Proteins; Mutation

Mutations in MBOAT7, Encoding Lysophosphatidylinositol Acyltransferase I, Lead to Intellectual Disability Accompanied by Epilepsy and Autistic Features. - Johansen, Anide; Rosti, Rasim O; Musaev, Damir; Sticca, Evan; Harripaul, Ricardo; Zaki, Maha; Çağlayan, Ahmet Okay; Azam, Matloob; Sultan, Tipu; Froukh, Tawfiq; Reis, André; Popp, Bernt; et al. (Am J Hum Genet, 2016)
The risk of epilepsy among individuals with intellectual disability (ID) is approximately ten times that of the general population. From a cohort of >5,000 families affected by neurodevelopmental disorders, we identified six consanguineous families harboring homozygous inactivating variants in MBOAT7, encoding lysophosphatidylinositol acyltransferase (LPIAT1). Subjects presented with ID frequently accompanied by epilepsy and autistic features. LPIAT1 is a membrane-bound phospholipid-remodeling enzyme that transfers arachidonic acid (AA) to lysophosphatidylinositol to produce AA-containing phosphatidylinositol. This study suggests a role for AA-containing phosphatidylinositols in the development of ID accompanied by epilepsy and autistic features.
Keywords: Acyltransferases; Arachidonic Acid; Autistic Disorder; Child; Child, Preschool; Consanguinity; Epilepsy; Female; Homozygote; Humans; Infant; Intellectual Disability; Lysophospholipids; Male; Membrane Proteins; Mutation; Pedigree; Phosphatidylinositols

Mutations in nuclear pore genes NUP93, NUP205 and XPO5 cause steroid-resistant nephrotic syndrome. - Braun, Daniela A; Sadowski, Carolin E; Kohl, Stefan; Lovric, Svjetlana; Astrinidis, Susanne A; Pabst, Werner L; Gee, Heon Yung; Ashraf, Shazia; Lawson, Jennifer A; Shril, Shirlee; Airik, Merlin; Tan, Weizhen; et al. (Nat Genet, 2016)
Nucleoporins are essential components of the nuclear pore complex (NPC). Only a few diseases have been attributed to NPC dysfunction. Steroid-resistant nephrotic syndrome (SRNS), a frequent cause of chronic kidney disease, is caused by dysfunction of glomerular podocytes. Here we identify in eight families with SRNS mutations in NUP93, its interaction partner NUP205 or XPO5 (encoding exportin 5) as hitherto unrecognized monogenic causes of SRNS. NUP93 mutations caused disrupted NPC assembly. NUP93 knockdown reduced the presence of NUP205 in the NPC, and, reciprocally, a NUP205 alteration abrogated NUP93 interaction. We demonstrate that NUP93 and exportin 5 interact with the signaling protein SMAD4 and that NUP93 mutations abrogated interaction with SMAD4. Notably, NUP93 mutations interfered with BMP7-induced SMAD transcriptional reporter activity. We hereby demonstrate that mutations of NUP genes cause a distinct renal disease and identify aberrant SMAD signaling as a new disease mechanism of SRNS, opening a potential new avenue for treatment.
Keywords: Age of Onset; Amino Acid Sequence; Animals; Cell Movement; Cell Proliferation; Cells, Cultured; Child; Child, Preschool; Drug Resistance; Female; Genes, Recessive; Genetic Association Studies; Genetic Linkage; HEK293 Cells; Humans; Infant; Karyopherins; Male; Mice; Molecular Sequence Data; Mutation; Nephrotic Syndrome; Nuclear Pore Complex Proteins; Oxidative Stress; Podocytes; Sequence Analysis, DNA; Steroids; Xenopus laevis

Mutations in the Histone Modifier PRDM6 Are Associated with Isolated Nonsyndromic Patent Ductus Arteriosus. - Li, Na; Subrahmanyan, Lakshman; Smith, Emily; Yu, Xiaoqing; Zaidi, Samir; Choi, Murim; Mane, Shrikant; Nelson-Williams, Carol; Behjati, Mohaddeseh; Kazemi, Mohammad; Hashemi, Mohammad; Fathzadeh, Mohsen; et al. (Am J Hum Genet, 2016)
Nonsyndromic patent ductus arteriosus (PDA) is a common congenital heart defect (CHD) with both inherited and acquired causes, but the disease mechanisms have remained elusive. Using combined genome-wide linkage analysis and whole-exome sequencing (WES), we identified independent mutations in PRDM6, which encodes a nuclear protein that is specific to vascular smooth muscle cells (VSMC), has histone methyl transferase activities, and acts as a transcriptional suppressor of contractile proteins. In vitro assays showed that the mutations cause loss of function either by intracellular redistribution of the protein and/or by alteration of its methyltransferase activities. Wild-type embryonic ductus arteriosus (DA) exhibited high levels of PRDM6, which rapidly declined postnatally as the number of VSMCs necessary for ductus contraction increased. This dynamic change suggests that PRDM6 plays a key role in maintaining VSMCs in an undifferentiated stage in order to promote their proliferation and that its loss of activity results in premature differentiation and impaired remodeling of the DA. Our findings identify PRDM6 mutations as underlying genetic causes of nonsyndromic isolated PDA in humans and implicates the wild-type protein in epigenetic regulation of ductus remodeling.
Keywords: Cell Differentiation; Cells, Cultured; Ductus Arteriosus, Patent; Epigenesis, Genetic; Female; Fluorescent Antibody Technique; Histones; Humans; Immunoblotting; Male; Muscle Proteins; Muscle, Smooth, Vascular; Mutation; Pedigree; Transcription Factors

Mutations in the nuclear bile acid receptor FXR cause progressive familial intrahepatic cholestasis. - Gomez-Ospina, Natalia; Potter, Carol J; Xiao, Rui; Manickam, Kandamurugu; Kim, Mi-Sun; Kim, Kang Ho; Shneider, Benjamin L; Picarsic, Jennifer L; Jacobson, Theodora A; Zhang, Jing; He, Weimin; Liu, Pengfei; et al. (Nat Commun, 2016)
Neonatal cholestasis is a potentially life-threatening condition requiring prompt diagnosis. Mutations in several different genes can cause progressive familial intrahepatic cholestasis, but known genes cannot account for all familial cases. Here we report four individuals from two unrelated families with neonatal cholestasis and mutations in NR1H4, which encodes the farnesoid X receptor (FXR), a bile acid-activated nuclear hormone receptor that regulates bile acid metabolism. Clinical features of severe, persistent NR1H4-related cholestasis include neonatal onset with rapid progression to end-stage liver disease, vitamin K-independent coagulopathy, low-to-normal serum gamma-glutamyl transferase activity, elevated serum alpha-fetoprotein and undetectable liver bile salt export pump (ABCB11) expression. Our findings demonstrate a pivotal function for FXR in bile acid homeostasis and liver protection.
Keywords: ATP Binding Cassette Transporter, Subfamily B, Member 11; ATP-Binding Cassette Transporters; Bile Acids and Salts; Cholestasis, Intrahepatic; Female; Humans; Male; Mutation; Receptors, Cytoplasmic and Nuclear; Young Adult

Nonrecurrent PMP22-RAI1 contiguous gene deletions arise from replication-based mechanisms and result in Smith-Magenis syndrome with evident peripheral neuropathy. - Yuan, Bo; Neira, Juanita; Gu, Shen; Harel, Tamar; Liu, Pengfei; Briceño, Ignacio; Elsea, Sarah H; Gómez, Alberto; Potocki, Lorraine; Lupski, James R (Hum Genet, 2016)
Hereditary neuropathy with liability to pressure palsies (HNPP) and Smith-Magenis syndrome (SMS) are genomic disorders associated with deletion copy number variants involving chromosome 17p12 and 17p11.2, respectively. Nonallelic homologous recombination (NAHR)-mediated recurrent deletions are responsible for the majority of HNPP and SMS cases; the rearrangement products encompass the key dosage-sensitive genes PMP22 and RAI1, respectively, and result in haploinsufficiency for these genes. Less frequently, nonrecurrent genomic rearrangements occur at this locus. Contiguous gene duplications encompassing both PMP22 and RAI1, i.e., PMP22-RAI1 duplications, have been investigated, and replication-based mechanisms rather than NAHR have been proposed for these rearrangements. In the current study, we report molecular and clinical characterizations of six subjects with the reciprocal phenomenon of deletions spanning both genes, i.e., PMP22-RAI1 deletions. Molecular studies utilizing high-resolution array comparative genomic hybridization and breakpoint junction sequencing identified mutational signatures that were suggestive of replication-based mechanisms. Systematic clinical studies revealed features consistent with SMS, including features of intellectual disability, speech and gross motor delays, behavioral problems and ocular abnormalities. Five out of six subjects presented clinical signs and/or objective electrophysiologic studies of peripheral neuropathy. Clinical profiling may improve the clinical management of this unique group of subjects, as the peripheral neuropathy can be more severe or of earlier onset as compared to SMS patients having the common recurrent deletion. Moreover, the current study, in combination with the previous report of PMP22-RAI1 duplications, contributes to the understanding of rare complex phenotypes involving multiple dosage-sensitive genes from a genetic mechanistic standpoint.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosomes, Human, Pair 17; DNA Copy Number Variations; DNA Replication; Female; Gene Deletion; Haploinsufficiency; Homologous Recombination; Humans; Intellectual Disability; Male; Mutation; Myelin Proteins; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors

Novel genetic causes for cerebral visual impairment. - Bosch, Daniëlle G M; Boonstra, F Nienke; de Leeuw, Nicole; Pfundt, Rolph; Nillesen, Willy M; de Ligt, Joep; Gilissen, Christian; Jhangiani, Shalini; Lupski, James R; Cremers, Frans P M; de Vries, Bert B A (Eur J Hum Genet, 2016)
Cerebral visual impairment (CVI) is a major cause of low vision in children due to impairment in projection and/or interpretation of the visual input in the brain. Although acquired causes for CVI are well known, genetic causes underlying CVI are largely unidentified. DNAs of 25 patients with CVI and intellectual disability, but without acquired (eg, perinatal) damage, were investigated by whole-exome sequencing. The data were analyzed for de novo, autosomal-recessive, and X-linked variants, and subsequently classified into known, candidate, or unlikely to be associated with CVI. This classification was based on the Online Mendelian Inheritance in Man database, literature reports, variant characteristics, and functional relevance of the gene. After classification, variants in four genes known to be associated with CVI (AHDC1, NGLY1, NR2F1, PGAP1) in 5 patients (20%) were identified, establishing a conclusive genetic diagnosis for CVI. In addition, in 11 patients (44%) with CVI, variants in one or more candidate genes were identified (ACP6, AMOT, ARHGEF10L, ATP6V1A, DCAF6, DLG4, GABRB2, GRIN1, GRIN2B, KCNQ3, KCTD19, RERE, SLC1A1, SLC25A16, SLC35A2, SOX5, UFSP2, UHMK1, ZFP30). Our findings show that diverse genetic causes underlie CVI, some of which will provide insight into the biology underlying this disease process.
Keywords: Adolescent; Blindness, Cortical; Child; Child, Preschool; Female; Genetic Loci; Humans; Male; Polymorphism, Single Nucleotide; Young Adult

A novel missense variant in the PNPLA1 gene underlies congenital ichthyosis in three consanguineous families. - Ahmad, F; Ansar, M; Mehmood, S; Izoduwa, A; Lee, K; Nasir, A; Abrar, M; Mehmood, S; Ullah, A; Aziz, A; Smith, J D; Shendure, J; et al. (J Eur Acad Dermatol Venereol, 2016)
Keywords: Amino Acid Sequence; Consanguinity; Female; Genes, Recessive; Humans; Ichthyosiform Erythroderma, Congenital; Lipase; Male; Mutation, Missense; Pakistan; Pedigree; Sequence Homology, Amino Acid

Novel mutations in LRP6 highlight the role of WNT signaling in tooth agenesis. - Ockeloen, Charlotte W; Khandelwal, Kriti D; Dreesen, Karoline; Ludwig, Kerstin U; Sullivan, Robert; van Rooij, Iris A L M; Thonissen, Michelle; Swinnen, Steven; Phan, Milien; Conte, Federica; Ishorst, Nina; Gilissen, Christian; et al. (Genet Med, 2016)
PURPOSE: We aimed to identify a novel genetic cause of tooth agenesis (TA) and/or orofacial clefting (OFC) by combining whole-exome sequencing (WES) and targeted resequencing in a large cohort of TA and OFC patients. METHODS: WES was performed in two unrelated patients: one with severe TA and OFC and another with severe TA only. After deleterious mutations were identified in a gene encoding low-density lipoprotein receptor-related protein 6 (LRP6), all its exons were resequenced with molecular inversion probes in 67 patients with TA, 1,072 patients with OFC, and 706 controls. RESULTS: We identified a frameshift (c.4594delG, p.Cys1532fs) and a canonical splice-site mutation (c.3398-2A>C, p.?) in LRP6, respectively, in the patient with TA and OFC and in the patient with severe TA only. The targeted resequencing showed significant enrichment of unique LRP6 variants in TA patients but not in nonsyndromic OFC patients. Of the five variants in patients with TA, two affected the canonical splice site and three were missense variants; all variants segregated with the dominant phenotype, and in one case the missense mutation occurred de novo. CONCLUSION: Mutations in LRP6 cause TA in humans.Genet Med 18 11, 1158-1162.
Keywords: Adolescent; Anodontia; Child; Exome; Female; Frameshift Mutation; Genetic Predisposition to Disease; Humans; Low Density Lipoprotein Receptor-Related Protein-6; Male; Mutation, Missense; Pedigree; Sequence Analysis, DNA; Wnt Signaling Pathway

Novel mutations in the genes TGM1 and ALOXE3 underlying autosomal recessive congenital ichthyosis. - Ullah, Rahim; Ansar, Muhammad; Durrani, Zaka Ullah; Lee, Kwanghyuk; Santos-Cortez, Regie Lyn P; Muhammad, Dost; Ali, Mahboob; Zia, Muhammad; Ayub, Muhammad; Khan, Suliman; Smith, Josh D; Nickerson, Deborah A; et al. (Int J Dermatol, 2016)
BACKGROUND: Ichthyoses are clinically characterized by scaling or hyperkeratosis of the skin or both. It can be an isolated condition limited to the skin or appear secondarily with involvement of other cutaneous or systemic abnormalities. METHODS: The present study investigated clinical and molecular characterization of three consanguineous families (A, B, C) segregating two different forms of autosomal recessive congenital ichthyosis (ARCI). Linkage in three consanguineous families (A, B, C) segregating two different forms of ARCI was searched by typing microsatellite and single nucleotide polymorphism marker analysis. Sequencing of the two genes TGM1 and ALOXE3 was performed by the dideoxy chain termination method. RESULTS: Genome-wide linkage analysis established linkage in family A to TGM1 gene on chromosome 14q11 and in families B and C to ALOXE3 gene on chromosome 17p13. Subsequently, sequencing of these genes using samples from affected family members led to the identification of three novel mutations: a missense variant p.Trp455Arg in TGM1 (family A); a nonsense variant p.Arg140* in ALOXE3 (family B); and a complex rearrangement in ALOXE3 (family C). CONCLUSION: The present study further extends the spectrum of mutations in the two genes involved in causing ARCI. Characterizing the clinical spectrum resulting from mutations in the TGM1 and ALOXE3 genes will improve diagnosis and may direct clinical care of the family members.
Keywords: Adolescent; Chromosomes, Human, Pair 14; Chromosomes, Human, Pair 17; Codon, Nonsense; Consanguinity; Female; Gene Rearrangement; Genotype; Humans; Ichthyosiform Erythroderma, Congenital; Ichthyosis, Lamellar; Lipoxygenase; Male; Mutation, Missense; Pakistan; Pedigree; Phenotype; Transglutaminases; Young Adult

Overlapping 16p13.11 deletion and gain of copies variations associated with childhood onset psychosis include genes with mechanistic implications for autism associated pathways: Two case reports. - Brownstein, Catherine A; Kleiman, Robin J; Engle, Elizabeth C; Towne, Meghan C; D'Angelo, Eugene J; Yu, Timothy W; Beggs, Alan H; Picker, Jonathan; Fogler, Jason M; Carroll, Devon; Schmitt, Rachel C O; Wolff, Robert R; et al. (Am J Med Genet A, 2016)
Copy number variability at 16p13.11 has been associated with intellectual disability, autism, schizophrenia, epilepsy, and attention-deficit hyperactivity disorder. Adolescent/adult- onset psychosis has been reported in a subset of these cases. Here, we report on two children with CNVs in 16p13.11 that developed psychosis before the age of 7. The genotype and neuropsychiatric abnormalities of these patients highlight several overlapping genes that have possible mechanistic relevance to pathways previously implicated in Autism Spectrum Disorders, including the mTOR signaling and the ubiquitin-proteasome cascades. A careful screening of the 16p13.11 region is warranted in patients with childhood onset psychosis.
Keywords: Autistic Disorder; Child; Child, Preschool; Chromosome Deletion; Chromosomes, Human, Pair 16; Comparative Genomic Hybridization; Developmental Disabilities; DNA Copy Number Variations; Female; Genetic Association Studies; Humans; Male; Psychotic Disorders; Schizophrenia; Signal Transduction

PADRE: Pedigree-Aware Distant-Relationship Estimation. - Staples, Jeffrey; Witherspoon, David J; Jorde, Lynn B; Nickerson, Deborah A; Below, Jennifer E; Huff, Chad D (Am J Hum Genet, 2016)
Accurate estimation of shared ancestry is an important component of many genetic studies; current prediction tools accurately estimate pairwise genetic relationships up to the ninth degree. Pedigree-aware distant-relationship estimation (PADRE) combines relationship likelihoods generated by estimation of recent shared ancestry (ERSA) with likelihoods from family networks reconstructed by pedigree reconstruction and identification of a maximum unrelated set (PRIMUS), improving the power to detect distant relationships between pedigrees. Using PADRE, we estimated relationships from simulated pedigrees and three extended pedigrees, correctly predicting 20% more fourth- through ninth-degree simulated relationships than when using ERSA alone. By leveraging pedigree information, PADRE can even identify genealogical relationships between individuals who are genetically unrelated. For example, although 95% of 13(th)-degree relatives are genetically unrelated, in simulations, PADRE correctly predicted 50% of 13(th)-degree relationships to within one degree of relatedness. The improvement in prediction accuracy was consistent between simulated and actual pedigrees. We also applied PADRE to the HapMap3 CEU samples and report new cryptic relationships and validation of previously described relationships between families. PADRE greatly expands the range of relationships that can be estimated by using genetic data in pedigrees.
Keywords: Algorithms; Female; Haplotypes; Humans; Male; Models, Genetic; Pedigree; Reproducibility of Results

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins. - Szafranski, Przemyslaw; Gambin, Tomasz; Dharmadhikari, Avinash V; Akdemir, Kadir Caner; Jhangiani, Shalini N; Schuette, Jennifer; Godiwala, Nihal; Yatsenko, Svetlana A; Sebastian, Jessica; Madan-Khetarpal, Suneeta; Surti, Urvashi; Abellar, Rosanna G; et al. (Hum Genet, 2016)
Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a lethal lung developmental disorder caused by heterozygous point mutations or genomic deletion copy-number variants (CNVs) of FOXF1 or its upstream enhancer involving fetal lung-expressed long noncoding RNA genes LINC01081 and LINC01082. Using custom-designed array comparative genomic hybridization, Sanger sequencing, whole exome sequencing (WES), and bioinformatic analyses, we studied 22 new unrelated families (20 postnatal and two prenatal) with clinically diagnosed ACDMPV. We describe novel deletion CNVs at the FOXF1 locus in 13 unrelated ACDMPV patients. Together with the previously reported cases, all 31 genomic deletions in 16q24.1, pathogenic for ACDMPV, for which parental origin was determined, arose de novo with 30 of them occurring on the maternally inherited chromosome 16, strongly implicating genomic imprinting of the FOXF1 locus in human lungs. Surprisingly, we have also identified four ACDMPV families with the pathogenic variants in the FOXF1 locus that arose on paternal chromosome 16. Interestingly, a combination of the severe cardiac defects, including hypoplastic left heart, and single umbilical artery were observed only in children with deletion CNVs involving FOXF1 and its upstream enhancer. Our data demonstrate that genomic imprinting at 16q24.1 plays an important role in variable ACDMPV manifestation likely through long-range regulation of FOXF1 expression, and may be also responsible for key phenotypic features of maternal uniparental disomy 16. Moreover, in one family, WES revealed a de novo missense variant in ESRP1, potentially implicating FGF signaling in the etiology of ACDMPV.
Keywords: Chromosomes, Human, Pair 16; Comparative Genomic Hybridization; Female; Forkhead Transcription Factors; Genes, Lethal; Genome, Human; Genomic Imprinting; High-Throughput Nucleotide Sequencing; Humans; Infant, Newborn; Male; Pedigree; Persistent Fetal Circulation Syndrome; Pulmonary Alveoli; Pulmonary Veins; Sequence Deletion

Pathogenic FBN1 variants in familial thoracic aortic aneurysms and dissections. - Regalado, E S; Guo, D C; Santos-Cortez, R L P; Hostetler, E; Bensend, T A; Pannu, H; Estrera, A; Safi, H; Mitchell, A L; Evans, J P; Leal, S M; Bamshad, M; et al. (Clin Genet, 2016)
Marfan syndrome (MFS) due to mutations in FBN1 is a known cause of thoracic aortic aneurysms and acute aortic dissections (TAAD) associated with pleiotropic manifestations. Genetic predisposition to TAAD can also be inherited in families in the absence of syndromic features, termed familial TAAD (FTAAD), and several causative genes have been identified to date. FBN1 mutations can also be identified in FTAAD families, but the frequency of these mutations has not been established. We performed exome sequencing of 183 FTAAD families and identified pathogenic FBN1 variants in five (2.7%) of these families. We also identified eight additional FBN1 rare variants that could not be unequivocally classified as disease-causing in six families. FBN1 sequencing should be considered in individuals with FTAAD even without significant systemic features of MFS.
Keywords: Adult; Aged; Aneurysm, Dissecting; Aortic Aneurysm, Thoracic; Exome; Family Health; Female; Fibrillin-1; Genetic Predisposition to Disease; Humans; Male; Marfan Syndrome; Middle Aged; Mutation; Pedigree; Sequence Analysis, DNA

A patient with a novel homozygous missense mutation in FTO and concomitant nonsense mutation in CETP. - Çağlayan, Ahmet O; Tuysuz, Beyhan; Coşkun, Süleyman; Quon, Jennifer; Harmancı, Akdes S; Baranoski, Jacob F; Baran, Burçin; Erson-Omay, E Zeynep; Henegariu, Octavian; Mane, Shrikant M; Bilguvar, Kaya; Yasuno, Katsuhito; et al. (J Hum Genet, 2016)
The fat mass and obesity associated (FTO) gene has previously been associated with a variety of diseases and conditions, notably obesity, acute coronary syndrome and metabolic syndrome. Reports describing mutations in FTO as well as in FTO animal models have further demonstrated a role for FTO in the development of the brain and other organs. Here, we describe a patient born of consanguineous union who presented with microcephaly, developmental delay, behavioral abnormalities, dysmorphic facial features, hypotonia and other various phenotypic abnormalities. Whole-exome sequencing revealed a novel homozygous missense mutation in FTO and a nonsense mutation in the cholesteryl ester transfer protein (CETP). Exome copy number variation analysis revealed no disease-causing large duplications or deletions within coding regions. Patient's, her parents' and non-related control' fibroblasts were analyzed for morphologic defects, abnormal proliferation, apoptosis and transcriptome profile. We have shown that FTO is located in the nucleus of cells from each tested sample. Western blot analysis demonstrated no changes in patient FTO. Quantitative (qPCR) analysis revealed slightly decreased levels of FTO expression in patient cells compared with controls. No morphological or proliferation differences between the patient and control fibroblasts were observed. There is still much to be learned about the molecular mechanisms by which mutations in FTO contribute to such severe phenotypes.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Apoptosis; Biopsy; Child, Preschool; Cholesterol Ester Transfer Proteins; Computational Biology; Consanguinity; DNA Copy Number Variations; DNA Mutational Analysis; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Association Studies; Genotype; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Mutation, Missense; Phenotype; Transcriptome

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies. - Gawlinski, Pawel; Posmyk, Renata; Gambin, Tomasz; Sielicka, Danuta; Chorazy, Monika; Nowakowska, Beata; Jhangiani, Shalini N; Muzny, Donna M; Bekiesinska-Figatowska, Monika; Bal, Jerzy; Boerwinkle, Eric; Gibbs, Richard A; et al. (Pediatr Neurol, 2016)
BACKGROUND: Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS: We enrolled two patients with a prior diagnosis of PEHO and two individuals with PEHO-like syndrome. All four individuals subsequently underwent whole-exome sequencing and comprehensive genomic analysis. RESULTS: We identified disease-causing mutations in known genes associated with neurodevelopmental disorders including GNAO1 and CDKL5 in two of four individuals. One patient with PEHO syndrome and a de novoGNAO1 mutation was found to have an additional de novo mutation in HESX1 that is associated with optic atrophy. CONCLUSIONS: We hypothesize that PEHO and PEHO-like syndrome may represent a severe end of the spectrum of the early-onset encephalopathies and, in some instances, its complex phenotype may result from an aggregated effect of mutations at two loci.
Keywords: Brain Edema; Child; Child, Preschool; Female; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; Infant; Male; Mutation; Neurodegenerative Diseases; Optic Atrophy; Phenotype; Protein Serine-Threonine Kinases; Spasms, Infantile

Periodontal Ehlers-Danlos Syndrome Is Caused by Mutations in C1R and C1S, which Encode Subcomponents C1r and C1s of Complement. - Kapferer-Seebacher, Ines; Pepin, Melanie; Werner, Roland; Aitman, Timothy J; Nordgren, Ann; Stoiber, Heribert; Thielens, Nicole; Gaboriaud, Christine; Amberger, Albert; Schossig, Anna; Gruber, Robert; Giunta, Cecilia; et al. (Am J Hum Genet, 2016)
Periodontal Ehlers-Danlos syndrome (pEDS) is an autosomal-dominant disorder characterized by early-onset periodontitis leading to premature loss of teeth, joint hypermobility, and mild skin findings. A locus was mapped to an approximately 5.8 Mb region at 12p13.1 but no candidate gene was identified. In an international consortium we recruited 19 independent families comprising 107 individuals with pEDS to identify the locus, characterize the clinical details in those with defined genetic causes, and try to understand the physiological basis of the condition. In 17 of these families, we identified heterozygous missense or in-frame insertion/deletion mutations in C1R (15 families) or C1S (2 families), contiguous genes in the mapped locus that encode subunits C1r and C1s of the first component of the classical complement pathway. These two proteins form a heterotetramer that then combines with six C1q subunits. Pathogenic variants involve the subunit interfaces or inter-domain hinges of C1r and C1s and are associated with intracellular retention and mild endoplasmic reticulum enlargement. Clinical features of affected individuals in these families include rapidly progressing periodontitis with onset in the teens or childhood, a previously unrecognized lack of attached gingiva, pretibial hyperpigmentation, skin and vascular fragility, easy bruising, and variable musculoskeletal symptoms. Our findings open a connection between the inflammatory classical complement pathway and connective tissue homeostasis.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosome Mapping; Chromosomes, Human, Pair 12; Complement C1r; Complement C1s; Ehlers-Danlos Syndrome; Endoplasmic Reticulum; Exome; Female; Gene Deletion; Genetic Loci; Humans; Male; Mutation, Missense; Pedigree; Periodontitis; Protein Conformation; Young Adult

Phenotypic Expansion of Congenital Disorder of Glycosylation Due to SRD5A3 Null Mutation. - Tuysuz, Beyhan; Pehlivan, Davut; Özkök, Ahmet; Jhangiani, Shalini; Yalcinkaya, Cengiz; Zeybek, Çiğdem Aktuğlu; Muzny, Donna Marie; Lupski, James R; Gibbs, Richard; Jaeken, Jaak (JIMD Rep, 2016)
We present a boy, admitted at 4 months, with facial dysmorphism, hypertrichosis, loose skin, bilateral inguinal hernia, severe hypotonia, psychomotor disability, seizures with hypsarrhythmia (West syndrome), hepatosplenomegaly, increased serum transaminases, iris coloboma, glaucoma, corneal clouding and bilateral dilated lateral ventricles, and extra-axial post-cerebellar space. Serum transferrin isoelectrofocusing (IEF) showed a type 1 pattern. Whole-exome genotyping showed a previously reported homozygous nonsense mutation c.320G>A; p.Trp107X in SRD5A3. Epilepsy and glaucoma have been reported only once in the 19 described SRD5A3-congenital glycosylation defect patients, and corneal clouding not at all.

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

PRIMUS: improving pedigree reconstruction using mitochondrial and Y haplotypes. - Staples, Jeffrey; Ekunwe, Lynette; Lange, Ethan; Wilson, James G; Nickerson, Deborah A; Below, Jennifer E (Bioinformatics, 2016)
UNLABELLED: PRIMUS is a pedigree reconstruction algorithm that uses estimates of genome-wide identity by descent to reconstruct pedigrees consistent with observed genetic data. However, when genetic data for individuals within a pedigree are missing, often multiple pedigrees can be reconstructed that fit the data. We report a major expansion of PRIMUS that uses mitochondrial (mtDNA) and non-recombining Y chromosome (NRY) haplotypes to eliminate many pedigree structures that are inconsistent with the genetic data. We demonstrate that discordances in mtDNA and NRY haplotypes substantially reduce the number of potential pedigrees, and often lead to the identification of the correct pedigree. AVAILABILITY AND IMPLEMENTATION: We have implemented PRIMUS updates in PERL and it is available at primus.gs.washington.edu.
Keywords: Algorithms; Chromosomes, Human, Y; Computer Simulation; DNA, Mitochondrial; Genetics, Population; Haplotypes; Humans; Linkage Disequilibrium; Pedigree; Software

PYCR2 Mutations cause a lethal syndrome of microcephaly and failure to thrive. - Zaki, Maha S; Bhat, Gifty; Sultan, Tipu; Issa, Mahmoud; Jung, Hea-Jin; Dikoglu, Esra; Selim, Laila; G Mahmoud, Imam; Abdel-Hamid, Mohamed S; Abdel-Salam, Ghada; Marin-Valencia, Isaac; Gleeson, Joseph G (Ann Neurol, 2016)
OBJECTIVE: A study was undertaken to characterize the clinical features of the newly described hypomyelinating leukodystrophy type 10 with microcephaly. This is an autosomal recessive disorder mapped to chromosome 1q42.12 due to mutations in the PYCR2 gene, encoding an enzyme involved in proline synthesis in mitochondria. METHODS: From several international clinics, 11 consanguineous families were identified with PYCR2 mutations by whole exome or targeted sequencing, with detailed clinical and radiological phenotyping. Selective mutations from patients were tested for effect on protein function. RESULTS: The characteristic clinical presentation of patients with PYCR2 mutations included failure to thrive, microcephaly, craniofacial dysmorphism, progressive psychomotor disability, hyperkinetic movements, and axial hypotonia with variable appendicular spasticity. Patients did not survive beyond the first decade of life. Brain magnetic resonance imaging showed global brain atrophy and white matter T2 hyperintensities. Routine serum metabolic profiles were unremarkable. Both nonsense and missense mutations were identified, which impaired protein multimerization. INTERPRETATION: PYCR2-related syndrome represents a clinically recognizable condition in which PYCR2 mutations lead to protein dysfunction, not detectable on routine biochemical assessments. Mutations predict a poor outcome, probably as a result of impaired mitochondrial function. Ann Neurol 2016;80:59-70.
Keywords: Adolescent; Child; Child, Preschool; Codon, Nonsense; Exome; Failure to Thrive; Female; Fibroblasts; Gene Expression; Genetic Predisposition to Disease; Genotype; Humans; Infant; Male; Microcephaly; Mutation, Missense; Phenotype; Primary Cell Culture; Pyrroline Carboxylate Reductases; Syndrome; Transfection; Young Adult

Rapid molecular diagnostics of severe primary immunodeficiency determined by using targeted next-generation sequencing. - Yu, Hui; Zhang, Victor Wei; Stray-Pedersen, Asbjørg; Hanson, Imelda Celine; Forbes, Lisa R; de la Morena, M Teresa; Chinn, Ivan K; Gorman, Elizabeth; Mendelsohn, Nancy J; Pozos, Tamara; Wiszniewski, Wojciech; Nicholas, Sarah K; et al. (J Allergy Clin Immunol, 2016)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are inherited disorders of the immune system. The most severe form, severe combined immunodeficiency (SCID), presents with profound deficiencies of T cells, B cells, or both at birth. If not treated promptly, affected patients usually do not live beyond infancy because of infections. Genetic heterogeneity of SCID frequently delays the diagnosis; a specific diagnosis is crucial for life-saving treatment and optimal management. OBJECTIVE: We developed a next-generation sequencing (NGS)-based multigene-targeted panel for SCID and other severe PIDDs requiring rapid therapeutic actions in a clinical laboratory setting. METHODS: The target gene capture/NGS assay provides an average read depth of approximately 1000×. The deep coverage facilitates simultaneous detection of single nucleotide variants and exonic copy number variants in one comprehensive assessment. Exons with insufficient coverage (<20× read depth) or high sequence homology (pseudogenes) are complemented by amplicon-based sequencing with specific primers to ensure 100% coverage of all targeted regions. RESULTS: Analysis of 20 patient samples with low T-cell receptor excision circle numbers on newborn screening or a positive family history or clinical suspicion of SCID or other severe PIDD identified deleterious mutations in 14 of them. Identified pathogenic variants included both single nucleotide variants and exonic copy number variants, such as hemizygous nonsense, frameshift, and missense changes in IL2RG; compound heterozygous changes in ATM, RAG1, and CIITA; homozygous changes in DCLRE1C and IL7R; and a heterozygous nonsense mutation in CHD7. CONCLUSION: High-throughput deep sequencing analysis with complete clinical validation greatly increases the diagnostic yield of severe primary immunodeficiency. Establishing a molecular diagnosis enables early immune reconstitution through prompt therapeutic intervention and guides management for improved long-term quality of life.
Keywords: Adolescent; Child; Female; Genetic Variation; Humans; Male; Pathology, Molecular; Sequence Analysis, DNA; Severe Combined Immunodeficiency

Recessive Inactivating Mutations in TBCK, Encoding a Rab GTPase-Activating Protein, Cause Severe Infantile Syndromic Encephalopathy. - Chong, Jessica X; Caputo, Viviana; Phelps, Ian G; Stella, Lorenzo; Worgan, Lisa; Dempsey, Jennifer C; Nguyen, Alina; Leuzzi, Vincenzo; Webster, Richard; Pizzuti, Antonio; Marvin, Colby T; Ishak, Gisele E; et al. (Am J Hum Genet, 2016)
Infantile encephalopathies are a group of clinically and biologically heterogeneous disorders for which the genetic basis remains largely unknown. Here, we report a syndromic neonatal encephalopathy characterized by profound developmental disability, severe hypotonia, seizures, diminished respiratory drive requiring mechanical ventilation, brain atrophy, dysgenesis of the corpus callosum, cerebellar vermis hypoplasia, and facial dysmorphism. Biallelic inactivating mutations in TBCK (TBC1-domain-containing kinase) were independently identified by whole-exome sequencing as the cause of this condition in four unrelated families. Matching these families was facilitated by the sharing of phenotypic profiles and WES data in a recently released web-based tool (Geno2MP) that links phenotypic information to rare variants in families with Mendelian traits. TBCK is a putative GTPase-activating protein (GAP) for small GTPases of the Rab family and has been shown to control cell growth and proliferation, actin-cytoskeleton dynamics, and mTOR signaling. Two of the three mutations (c.376C>T [p.Arg126(∗)] and c.1363A>T [p.Lys455(∗)]) are predicted to truncate the protein, and loss of the major TBCK isoform was confirmed in primary fibroblasts from one affected individual. The third mutation, c.1532G>A (p.Arg511His), alters a conserved residue within the TBC1 domain. Structural analysis implicated Arg511 as a required residue for Rab-GAP function, and in silico homology modeling predicted impaired GAP function in the corresponding mutant. These results suggest that loss of Rab-GAP activity is the underlying mechanism of disease. In contrast to other disorders caused by dysregulated mTOR signaling associated with focal or global brain overgrowth, impaired TBCK function results in progressive loss of brain volume.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Brain Diseases; Child; Child, Preschool; Corpus Callosum; Female; GTPase-Activating Proteins; Humans; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Mutation; Pedigree; Protein Conformation; Protein-Serine-Threonine Kinases; Signal Transduction; TOR Serine-Threonine Kinases

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

Recurrent Muscle Weakness with Rhabdomyolysis, Metabolic Crises, and Cardiac Arrhythmia Due to Bi-allelic TANGO2 Mutations. - Lalani, Seema R; Liu, Pengfei; Rosenfeld, Jill A; Watkin, Levi B; Chiang, Theodore; Leduc, Magalie S; Zhu, Wenmiao; Ding, Yan; Pan, Shujuan; Vetrini, Francesco; Miyake, Christina Y; Shinawi, Marwan; et al. (Am J Hum Genet, 2016)
The underlying genetic etiology of rhabdomyolysis remains elusive in a significant fraction of individuals presenting with recurrent metabolic crises and muscle weakness. Using exome sequencing, we identified bi-allelic mutations in TANGO2 encoding transport and Golgi organization 2 homolog (Drosophila) in 12 subjects with episodic rhabdomyolysis, hypoglycemia, hyperammonemia, and susceptibility to life-threatening cardiac tachyarrhythmias. A recurrent homozygous c.460G>A (p.Gly154Arg) mutation was found in four unrelated individuals of Hispanic/Latino origin, and a homozygous ∼34 kb deletion affecting exons 3-9 was observed in two families of European ancestry. One individual of mixed Hispanic/European descent was found to be compound heterozygous for c.460G>A (p.Gly154Arg) and the deletion of exons 3-9. Additionally, a homozygous exons 4-6 deletion was identified in a consanguineous Middle Eastern Arab family. No homozygotes have been reported for these changes in control databases. Fibroblasts derived from a subject with the recurrent c.460G>A (p.Gly154Arg) mutation showed evidence of increased endoplasmic reticulum stress and a reduction in Golgi volume density in comparison to control. Our results show that the c.460G>A (p.Gly154Arg) mutation and the exons 3-9 heterozygous deletion in TANGO2 are recurrent pathogenic alleles present in the Latino/Hispanic and European populations, respectively, causing considerable morbidity in the homozygotes in these populations.
Keywords: Alleles; Arabs; Arrhythmias, Cardiac; Base Sequence; Child; Child, Preschool; Endoplasmic Reticulum Stress; European Continental Ancestry Group; Exome; Exons; Female; Gene Deletion; Golgi Apparatus; Hispanic Americans; Homozygote; Humans; Infant; Male; Molecular Sequence Data; Muscle Weakness; Pedigree; Rhabdomyolysis

Recurrent recessive mutation in deoxyguanosine kinase causes idiopathic noncirrhotic portal hypertension. - Vilarinho, Sílvia; Sari, Sinan; Yilmaz, Güldal; Stiegler, Amy L; Boggon, Titus J; Jain, Dhanpat; Akyol, Gülen; Dalgiç, Buket; Günel, Murat; Lifton, Richard P (Hepatology, 2016)
UNLABELLED: Despite advances in the diagnosis and management of idiopathic noncirrhotic portal hypertension, its pathogenesis remains elusive. Insight may be gained from study of early-onset familial idiopathic noncirrhotic portal hypertension, in which Mendelian mutations may account for disease. We performed exome sequencing of eight subjects from six kindreds with onset of portal hypertension of indeterminate etiology during infancy or childhood. Three subjects from two consanguineous families shared the identical rare homozygous p.N46S mutation in DGUOK, a deoxyguanosine kinase required for mitochondrial DNA replication; haplotype sharing demonstrated that the mutation in the two families was inherited from a remote common ancestor. All three affected subjects had stable portal hypertension with noncirrhotic liver disease for 6-16 years of follow-up. This mutation impairs adenosine triphosphate binding and reduces catalytic activity. Loss-of-function mutations in DGUOK have previously been implicated in cirrhosis and liver failure but not in isolated portal hypertension. Interestingly, treatment of patients with human immunodeficiency viral infection with the nucleoside analogue didanosine is known to cause portal hypertension in a subset of patients and lowers deoxyguanosine kinase levels in vitro; the current findings implicate these effects on deoxyguanosine kinase in the causal mechanism. CONCLUSION: Our findings provide new insight into the mechanisms mediating inherited and acquired noncirrhotic portal hypertension, expand the phenotypic spectrum of DGUOK deficiency, and provide a new genetic test for a specific cause of idiopathic noncirrhotic portal hypertension. (Hepatology 2016;63:1977-1986).
Keywords: Adolescent; Amino Acid Sequence; Animals; Cattle; Child; Child, Preschool; DNA Mutational Analysis; Dogs; Female; Genes, Recessive; Homozygote; Humans; Hypertension, Portal; Infant; Liver Failure; Male; Molecular Sequence Data; Pedigree; Phosphotransferases (Alcohol Group Acceptor); Principal Component Analysis; Rats; Young Adult

The role of combined SNV and CNV burden in patients with distal symmetric polyneuropathy. - Pehlivan, Davut; Beck, Christine R; Okamoto, Yuji; Harel, Tamar; Akdemir, Zeynep H C; Jhangiani, Shalini N; Withers, Marjorie A; Goksungur, Meryem Tuba; Carvalho, Claudia M B; Czesnik, Dirk; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; et al. (Genet Med, 2016)
PURPOSE: Charcot-Marie-Tooth (CMT) disease is a heterogeneous group of genetic disorders of the peripheral nervous system. Copy-number variants (CNVs) contribute significantly to CMT, as duplication of PMP22 underlies the majority of CMT1 cases. We hypothesized that CNVs and/or single-nucleotide variants (SNVs) might exist in patients with CMT with an unknown molecular genetic etiology. METHODS: Two hundred patients with CMT, negative for both SNV mutations in several CMT genes and for CNVs involving PMP22, were screened for CNVs by high-resolution oligonucleotide array comparative genomic hybridization. Whole-exome sequencing was conducted on individuals with rare, potentially pathogenic CNVs. RESULTS: Putatively causative CNVs were identified in five subjects (~2.5%); four of the five map to known neuropathy genes. Breakpoint sequencing revealed Alu-Alu-mediated junctions as a predominant contributor. Exome sequencing identified MFN2 SNVs in two of the individuals. CONCLUSION: Neuropathy-associated CNV outside of the PMP22 locus is rare in CMT. Nevertheless, there is potential clinical utility in testing for CNVs and exome sequencing in CMT cases negative for the CMT1A duplication. These findings suggest that complex phenotypes including neuropathy can potentially be caused by a combination of SNVs and CNVs affecting more than one disease-associated locus and contributing to a mutational burden.Genet Med 18 5, 443-451.
Keywords: Adult; Age of Onset; Charcot-Marie-Tooth Disease; Child, Preschool; Comparative Genomic Hybridization; DNA Copy Number Variations; Exome; Female; Genetic Predisposition to Disease; GTP Phosphohydrolases; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Motor Neurons; Myelin P0 Protein; Myelin Proteins; Neural Conduction; Polymorphism, Single Nucleotide; Polyneuropathies

Somatic mosaicism for a lethal TRPV4 mutation results in non-lethal metatropic dysplasia. - Weinstein, Michael M; Kang, Taekyu; Lachman, Ralph S; Bamshad, Michael; Nickerson, Deborah A; Krakow, Deborah; Cohn, Daniel H (Am J Med Genet A, 2016)
Dominant mutations in TRPV4, which encodes the Transient Receptor Potential Cation Channel Subfamily V Member 4 calcium channel, result in a series of musculoskeletal disorders that include a set of peripheral neuropathies and a broad phenotypic spectrum of skeletal dysplasias. The skeletal phenotypes range from brachyolmia, in which there is scoliosis with mild short stature, through perinatal lethal metatropic dysplasia. We describe a case with phenotypic findings consistent with metatropic dysplasia, but in whom no TRPV4 mutation was detected by Sanger sequence analysis. Exome sequence analysis identified a known lethal metatropic dysplasia mutation, TRPV4 , which was present at lower frequency than would be expected for a heterozygous change. The affected individual was shown to be a somatic mosaic for the mutation, providing an explanation for the milder than expected phenotype. The data illustrate that high-throughput sequencing of genomic DNA can facilitate detection of mosaicism with higher sensitivity than Sanger sequence analysis and identify a new genetic mechanism for metatropic dysplasia. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; DNA Mutational Analysis; Dwarfism; Exons; Genetic Association Studies; Humans; Infant; Magnetic Resonance Imaging; Mosaicism; Mutation; Osteochondrodysplasias; Phenotype; Physical Examination; Radiography; TRPV Cation Channels

Somatic mosaicism underlies X-linked acrogigantism syndrome in sporadic male subjects. - Daly, Adrian F; Yuan, Bo; Fina, Frederic; Caberg, Jean-Hubert; Trivellin, Giampaolo; Rostomyan, Liliya; de Herder, Wouter W; Naves, Luciana A; Metzger, Daniel; Cuny, Thomas; Rabl, Wolfgang; Shah, Nalini; et al. (Endocr Relat Cancer, 2016)
Somatic mosaicism has been implicated as a causative mechanism in a number of genetic and genomic disorders. X-linked acrogigantism (XLAG) syndrome is a recently characterized genomic form of pediatric gigantism due to aggressive pituitary tumors that is caused by submicroscopic chromosome Xq26.3 duplications that include GPR101 We studied XLAG syndrome patients (n= 18) to determine if somatic mosaicism contributed to the genomic pathophysiology. Eighteen subjects with XLAG syndrome caused by Xq26.3 duplications were identified using high-definition array comparative genomic hybridization (HD-aCGH). We noted that males with XLAG had a decreased log2ratio (LR) compared with expected values, suggesting potential mosaicism, whereas females showed no such decrease. Compared with familial male XLAG cases, sporadic males had more marked evidence for mosaicism, with levels of Xq26.3 duplication between 16.1 and 53.8%. These characteristics were replicated using a novel, personalized breakpoint junction-specific quantification droplet digital polymerase chain reaction (ddPCR) technique. Using a separate ddPCR technique, we studied the feasibility of identifying XLAG syndrome cases in a distinct patient population of 64 unrelated subjects with acromegaly/gigantism, and identified one female gigantism patient who had had increased copy number variation (CNV) threshold for GPR101 that was subsequently diagnosed as having XLAG syndrome on HD-aCGH. Employing a combination of HD-aCGH and novel ddPCR approaches, we have demonstrated, for the first time, that XLAG syndrome can be caused by variable degrees of somatic mosaicism for duplications at chromosome Xq26.3. Somatic mosaicism was shown to occur in sporadic males but not in females with XLAG syndrome, although the clinical characteristics of the disease were similarly severe in both sexes.
Keywords: Adult; Female; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Middle Aged; Mosaicism; Polymerase Chain Reaction; Syndrome; Young Adult

Somatic Mutations in NEK9 Cause Nevus Comedonicus. - Levinsohn, Jonathan L; Sugarman, Jeffrey L; McNiff, Jennifer M; Antaya, Richard J; Choate, Keith A (Am J Hum Genet, 2016)
Acne vulgaris (AV) affects most adolescents, and of those affected, moderate to severe disease occurs in 20%. Comedones, follicular plugs consisting of desquamated keratinocytes and sebum, are central to its pathogenesis. Despite high heritability in first-degree relatives, AV genetic determinants remain incompletely understood. We therefore employed whole-exome sequencing (WES) in nevus comedonicus (NC), a rare disorder that features comedones and inflammatory acne cysts in localized, linear configurations. WES identified somatic NEK9 mutations, each affecting highly conserved residues within its kinase or RCC1 domains, in affected tissue of three out of three NC-affected subjects. All mutations are gain of function, resulting in increased phosphorylation at Thr210, a hallmark of NEK9 kinase activation. We found that comedo formation in NC is marked by loss of follicular differentiation markers, expansion of keratin-15-positive cells from localization within the bulge to the entire sub-bulge follicle and cyst, and ectopic expression of keratin 10, a marker of interfollicular differentiation not present in normal follicles. These findings suggest that NEK9 mutations in NC disrupt normal follicular differentiation and identify NEK9 as a potential regulator of follicular homeostasis.
Keywords: Adolescent; Adult; Child; Female; Fluorescent Antibody Technique; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation; Nevus; NIMA-Related Kinases; Prognosis; Skin Neoplasms; Young Adult

SRD5A3-CDG: Expanding the phenotype of a congenital disorder of glycosylation with emphasis on adult onset features. - Wheeler, Patricia G; Ng, Bobby G; Sanford, Laura; Sutton, V Reid; Bartholomew, Dennis W; Pastore, Matthew T; Bamshad, Michael J; Kircher, Martin; Buckingham, Kati J; Nickerson, Deborah A; Shendure, Jay; Freeze, Hudson H (Am J Med Genet A, 2016)
Increasing numbers of congenital disorders of glycosylation (CDG) have been reported recently resulting in an expansion of the phenotypes associated with this group of disorders. SRD5A3 codes for polyprenol reductase which converts polyprenol to dolichol. This is a major pathway for dolichol biosynthesis for N-glycosylation, O-mannosylation, C-mannosylation, and GPI anchor synthesis. We present the features of five individuals (three children and two adults) with mutations in SRD5A3 focusing on the variable eye and skin involvement. We compare that to 13 affected individuals from the literature including five adults allowing us to delineate the features that may develop over time with this disorder including kyphosis, retinitis pigmentosa, and cataracts. © 2016 Wiley Periodicals, Inc.
Keywords: 3-Oxo-5-alpha-Steroid 4-Dehydrogenase; Adult; Child; Congenital Disorders of Glycosylation; Dolichols; Eye; Female; Glycosylation; Homozygote; Humans; Male; Membrane Proteins; Mutation; Phenotype; Skin; Tretinoin

A Syndromic Intellectual Disability Disorder Caused by Variants in TELO2, a Gene Encoding a Component of the TTT Complex. - You, Jing; Sobreira, Nara L; Gable, Dustin L; Jurgens, Julie; Grange, Dorothy K; Belnap, Newell; Siniard, Ashley; Szelinger, Szabolcs; Schrauwen, Isabelle; Richholt, Ryan F; Vallee, Stephanie E; Dinulos, Mary Beth P; et al. (Am J Hum Genet, 2016)
The proteins encoded by TELO2, TTI1, and TTI2 interact to form the TTT complex, a co-chaperone for maturation of the phosphatidylinositol 3-kinase-related protein kinases (PIKKs). Here we report six affected individuals from four families with intellectual disability (ID) and neurological and other congenital abnormalities associated with compound heterozygous variants in TELO2. Although their fibroblasts showed reduced steady-state levels of TELO2 and the other components of the TTT complex, PIKK functions were normal in cellular assays. Our results suggest that these TELO2 missense variants result in loss of function, perturb TTT complex stability, and cause an autosomal-recessive syndromic form of ID.
Keywords: Adolescent; Carrier Proteins; Child; Female; Humans; Intellectual Disability; Male; Molecular Chaperones; Pedigree; Phosphatidylinositol 3-Kinases; Protein-Serine-Threonine Kinases; Telomere-Binding Proteins

Two locus inheritance of non-syndromic midline craniosynostosis via rare and common alleles. - Timberlake, Andrew T; Choi, Jungmin; Zaidi, Samir; Lu, Qiongshi; Nelson-Williams, Carol; Brooks, Eric D; Bilguvar, Kaya; Tikhonova, Irina; Mane, Shrikant; Yang, Jenny F; Sawh-Martinez, Rajendra; Persing, Sarah; et al. (Elife, 2016)
Premature fusion of the cranial sutures (craniosynostosis), affecting 1 in 2000 newborns, is treated surgically in infancy to prevent adverse neurologic outcomes. To identify mutations contributing to common non-syndromic midline (sagittal and metopic) craniosynostosis, we performed exome sequencing of 132 parent-offspring trios and 59 additional probands. Thirteen probands (7%) had damaging de novo or rare transmitted mutations in , an inhibitor of BMP - induced osteoblast differentiation (p<10). mutations nonetheless showed striking incomplete penetrance (<60%). Genotypes of a common variant near that is strongly associated with midline craniosynostosis explained nearly all the phenotypic variation in these kindreds, with highly significant evidence of genetic interaction between these loci via both association and analysis of linkage. This epistatic interaction of rare and common variants defines the most frequent cause of midline craniosynostosis and has implications for the genetic basis of other diseases.
Keywords: Alleles; Bone Morphogenetic Protein 2; Craniosynostoses; Exome; Genetic Association Studies; Humans; Infant; Mutation; Penetrance; Sequence Analysis, DNA; Smad6 Protein

Two novel germline DDX41 mutations in a family with inherited myelodysplasia/acute myeloid leukemia. - Li, Ruijuan; Sobreira, Nara; Witmer, P Dane; Pratz, Keith W; Braunstein, Evan M (Haematologica, 2016)
Keywords: DEAD-box RNA Helicases; Family; Female; Germ-Line Mutation; Humans; Leukemia, Myeloid, Acute; Male; Myelodysplastic Syndromes; Neoplasm Proteins

Update on the Toriello-Carey syndrome. - Toriello, Helga V; Colley, Chelsey; Bamshad, Michael (Am J Med Genet A, 2016)
Toriello and Carey described a provisionally-unique syndrome comprised of agenesis of the corpus callosum, Pierre Robin anomaly, and a characteristic facial phenotype. Because the condition affected siblings, this entity was postulated to be an autosomal recessive multiple anomaly syndrome. Several patients were subsequently reported, and over time, it became apparent that the Toriello-Carey syndrome was etiologically heterogeneous. Based on previous reports, it is estimated that at least 20% of patients with a clinical diagnosis of Toriello-Carey syndrome have a chromosomal anomaly as the basis of the phenotype. However, no basis for the non-chromosomal cases has been found. This review summarizes the literature to date and provides speculation regarding the possible explanations for failing to find the cause of Toriello-Carey syndrome. © 2016 Wiley Periodicals, Inc.
Keywords: Agenesis of Corpus Callosum; Chromosome Aberrations; Craniofacial Abnormalities; Female; Genetic Association Studies; Heart Defects, Congenital; Humans; Limb Deformities, Congenital; Male; Phenotype; Pierre Robin Syndrome; Urogenital Abnormalities

Using Whole Exome Sequencing to Identify Candidate Genes With Rare Variants In Nonsyndromic Cleft Lip and Palate. - Aylward, Alana; Cai, Yi; Lee, Andrew; Blue, Elizabeth; Rabinowitz, Daniel; Haddad, Joseph (Genet Epidemiol, 2016)
Studies suggest that nonsyndromic cleft lip and palate (NSCLP) is polygenic with variable penetrance, presenting a challenge in identifying all causal genetic variants. Despite relatively high prevalence of NSCLP among Amerindian populations, no large whole exome sequencing (WES) studies have been completed in this population. Our goal was to identify candidate genes with rare genetic variants for NSCLP in a Honduran population using WES. WES was performed on two to four members of 27 multiplex Honduran families. Genetic variants with a minor allele frequency > 1% in reference databases were removed. Heterozygous variants consistent with dominant disease with incomplete penetrance were ascertained, and variants with predicted functional consequence were prioritized for analysis. Pedigree-specific P-values were calculated as the probability of all affected members in the pedigree being carriers, given that at least one is a carrier. Preliminary results identified 3,727 heterozygous rare variants; 1,282 were predicted to be functionally consequential. Twenty-three genes had variants of interest in ≥3 families, where some genes had different variants in each family, giving a total of 50 variants. Variant validation via Sanger sequencing of the families and unrelated unaffected controls excluded variants that were sequencing errors or common variants not in databases, leaving four genes with candidate variants in ≥3 families. Of these, candidate variants in two genes consistently segregate with NSCLP as a dominant variant with incomplete penetrance: ACSS2 and PHYH. Rare variants found at the same gene in all affected individuals in several families are likely to be directly related to NSCLP.
Keywords: Acetate-CoA Ligase; Alleles; Cleft Lip; Cleft Palate; Female; Gene Frequency; Genotype; Heterozygote; Hexokinase; High-Throughput Nucleotide Sequencing; Humans; Male; Mixed Function Oxygenases; Pedigree; Penetrance; Sequence Analysis, DNA; von Willebrand Factor

Variants in SKP1, PROB1, and IL17B genes at keratoconus 5q31.1-q35.3 susceptibility locus identified by whole-exome sequencing. - Karolak, Justyna A; Gambin, Tomasz; Pitarque, Jose A; Molinari, Andrea; Jhangiani, Shalini; Stankiewicz, Pawel; Lupski, James R; Gajecka, Marzena (Eur J Hum Genet, 2016)
Keratoconus (KTCN) is a protrusion and thinning of the cornea, resulting in impairment of visual function. The extreme genetic heterogeneity makes it difficult to discover factors unambiguously influencing the KTCN phenotype. In this study, we used whole-exome sequencing (WES) and Sanger sequencing to reduce the number of candidate genes at the 5q31.1-q35.3 locus and to prioritize other potentially relevant variants in an Ecuadorian family with KTCN. We applied WES in two affected KTCN individuals from the Ecuadorian family that showed a suggestive linkage between the KTCN phenotype and the 5q31.1-q35.3 locus. Putative variants identified by WES were further evaluated in this family using Sanger sequencing. Exome capture discovered a total of 173 rare (minor allele frequency <0.001 in control population) nonsynonymous variants in both affected individuals. Among them, 16 SNVs were selected for further evaluation. Segregation analysis revealed that variants c.475T>G in SKP1, c.671G>A in PROB1, and c.527G>A in IL17B in the 5q31.1-q35.3 linkage region, and c.850G>A in HKDC1 in the 10q22 locus completely segregated with the phenotype in the studied KTCN family. We demonstrate that a combination of various techniques significantly narrowed the studied genomic region and reduced the list of the putative exonic variants. Moreover, since this locus overlapped two other chromosomal regions previously recognized in distinct KTCN studies, our findings suggest that this 5q31.1-q35.3 locus might be linked with KTCN.
Keywords: Chromosomes, Human, Pair 5; Exome; Female; Gene Frequency; Genetic Linkage; Genetic Predisposition to Disease; Genome, Human; Hexokinase; High-Throughput Nucleotide Sequencing; Humans; Interleukin-17; Keratoconus; Male; Pedigree; Phenotype; Proteins; S-Phase Kinase-Associated Proteins

Variants in SLC18A3, vesicular acetylcholine transporter, cause congenital myasthenic syndrome. - O'Grady, Gina L; Verschuuren, Corien; Yuen, Michaela; Webster, Richard; Menezes, Manoj; Fock, Johanna M; Pride, Natalie; Best, Heather A; Benavides Damm, Tatiana; Turner, Christian; Lek, Monkol; Engel, Andrew G; et al. (Neurology, 2016)
OBJECTIVE: To describe the clinical and genetic characteristics of presynaptic congenital myasthenic syndrome secondary to biallelic variants in SLC18A3. METHODS: Individuals from 2 families were identified with biallelic variants in SLC18A3, the gene encoding the vesicular acetylcholine transporter (VAChT), through whole-exome sequencing. RESULTS: The patients demonstrated features seen in presynaptic congenital myasthenic syndrome, including ptosis, ophthalmoplegia, fatigable weakness, apneic crises, and deterioration of symptoms in cold water for patient 1. Both patients demonstrated moderate clinical improvement on pyridostigmine. Patient 1 had a broader phenotype, including learning difficulties and left ventricular dysfunction. Electrophysiologic studies were typical for a presynaptic defect. Both patients showed profound electrodecrement on low-frequency repetitive stimulation followed by a prolonged period of postactivation exhaustion. In patient 1, this was unmasked only after isometric contraction, a recognized feature of presynaptic disease, emphasizing the importance of activation procedures. CONCLUSIONS: VAChT is responsible for uptake of acetylcholine into presynaptic vesicles. The clinical and electrographic characteristics of the patients described are consistent with previously reported mouse models of VAChT deficiency. These findings make it very likely that defects in VAChT due to variants in SLC18A3 are a cause of congenital myasthenic syndrome in humans.
Keywords: Adolescent; Child; Diagnosis, Differential; Female; Genetic Variation; Humans; Male; Myasthenic Syndromes, Congenital; Vesicular Acetylcholine Transport Proteins

Variants in the Oxidoreductase PYROXD1 Cause Early-Onset Myopathy with Internalized Nuclei and Myofibrillar Disorganization. - O'Grady, Gina L; Best, Heather A; Sztal, Tamar E; Schartner, Vanessa; Sanjuan-Vazquez, Myriam; Donkervoort, Sandra; Abath Neto, Osorio; Sutton, Roger Bryan; Ilkovski, Biljana; Romero, Norma Beatriz; Stojkovic, Tanya; Dastgir, Jahannaz; et al. (Am J Hum Genet, 2016)
This study establishes PYROXD1 variants as a cause of early-onset myopathy and uses biospecimens and cell lines, yeast, and zebrafish models to elucidate the fundamental role of PYROXD1 in skeletal muscle. Exome sequencing identified recessive variants in PYROXD1 in nine probands from five families. Affected individuals presented in infancy or childhood with slowly progressive proximal and distal weakness, facial weakness, nasal speech, swallowing difficulties, and normal to moderately elevated creatine kinase. Distinctive histopathology showed abundant internalized nuclei, myofibrillar disorganization, desmin-positive inclusions, and thickened Z-bands. PYROXD1 is a nuclear-cytoplasmic pyridine nucleotide-disulphide reductase (PNDR). PNDRs are flavoproteins (FAD-binding) and catalyze pyridine-nucleotide-dependent (NAD/NADH) reduction of thiol residues in other proteins. Complementation experiments in yeast lacking glutathione reductase glr1 show that human PYROXD1 has reductase activity that is strongly impaired by the disease-associated missense mutations. Immunolocalization studies in human muscle and zebrafish myofibers demonstrate that PYROXD1 localizes to the nucleus and to striated sarcomeric compartments. Zebrafish with ryroxD1 knock-down recapitulate features of PYROXD1 myopathy with sarcomeric disorganization, myofibrillar aggregates, and marked swimming defect. We characterize variants in the oxidoreductase PYROXD1 as a cause of early-onset myopathy with distinctive histopathology and introduce altered redox regulation as a primary cause of congenital muscle disease.
Keywords: Amino Acid Sequence; Animals; Cell Nucleus; Cercopithecus aethiops; Cohort Studies; COS Cells; Creatine Kinase; Cytoplasm; Distal Myopathies; ELAV-Like Protein 4; Female; Flavoproteins; Gene Deletion; Genetic Variation; Genome-Wide Association Study; Glutathione Reductase; HEK293 Cells; Humans; Male; Muscle, Skeletal; Mutation, Missense; Myopathies, Structural, Congenital; Oxidoreductases; Pedigree; Protein Conformation; Saccharomyces cerevisiae Proteins; Zebrafish

Visceral myopathy: Clinical and molecular survey of a cohort of seven new patients and state of the art of overlapping phenotypes. - Moreno, Carolina Araujo; Metze, Konradin; Lomazi, Elizete Aparecida; Bertola, Débora Romeo; Barbosa, Ricardo Henrique Almeida; Cosentino, Viviana; Sobreira, Nara; Cavalcanti, Denise Pontes (Am J Med Genet A, 2016)
Visceral motility dysfunction is a key feature of genetic disorders such as megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS, MIM moved from 249210 to 155310), chronic intestinal pseudo-obstruction (CIPO, MIM609629), and multisystemic smooth muscle dysfunction syndrome (MSMDS, MIM613834). The genetic bases of these conditions recently begun to be clarified with the identification of pathogenic variants in ACTG2, ACTA2, and MYH11 in individuals with visceral motility dysfunction. The MMIHS was associated with the heterozygous variant in ACTG2 and homozygous variant in MYH11, while the heterozygous variant in ACTA2 was observed in patients with MSMDS. In this study, we describe the clinical data as well as the molecular investigation of seven individuals with visceral myopathy phenotypes. Five patients presented with MMIHS, including two siblings from consanguineous parents, one had CIPO, and the other had MSMDS. In three individuals with MMIHS and in one with CIPO we identified heterozygous variant in ACTG2, one being a novel variant (c.584C>T-p.Thr195Ile). In the individual with MSMDS we identified a heterozygous variant in ACTA2. We performed the whole-exome sequencing in one sibling with MMIHS and her parents; however, the pathogenic variant responsible for her phenotype could not be identified. These results reinforce the clinical and genetic heterogeneity of the visceral myopathies. Although many cases of MMIHS are associated with ACTG2 variants, we suggest that other genes, besides MYH11, could cause the MMIHS with autosomal recessive pattern. © 2016 Wiley Periodicals, Inc.
Keywords: Abnormalities, Multiple; Actins; Child, Preschool; Colon; Consanguinity; DNA Mutational Analysis; Fatal Outcome; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Intestinal Pseudo-Obstruction; Male; Mutation; Phenotype; Polymorphism, Single Nucleotide; Treatment Outcome; Ultrasonography, Prenatal; Urinary Bladder

A visual and curatorial approach to clinical variant prioritization and disease gene discovery in genome-wide diagnostics. - James, Regis A; Campbell, Ian M; Chen, Edward S; Boone, Philip M; Rao, Mitchell A; Bainbridge, Matthew N; Lupski, James R; Yang, Yaping; Eng, Christine M; Posey, Jennifer E; Shaw, Chad A (Genome Med, 2016)
BACKGROUND: Genome-wide data are increasingly important in the clinical evaluation of human disease. However, the large number of variants observed in individual patients challenges the efficiency and accuracy of diagnostic review. Recent work has shown that systematic integration of clinical phenotype data with genotype information can improve diagnostic workflows and prioritization of filtered rare variants. We have developed visually interactive, analytically transparent analysis software that leverages existing disease catalogs, such as the Online Mendelian Inheritance in Man database (OMIM) and the Human Phenotype Ontology (HPO), to integrate patient phenotype and variant data into ranked diagnostic alternatives. METHODS: Our tool, "OMIM Explorer" ( http://www.omimexplorer.com ), extends the biomedical application of semantic similarity methods beyond those reported in previous studies. The tool also provides a simple interface for translating free-text clinical notes into HPO terms, enabling clinical providers and geneticists to contribute phenotypes to the diagnostic process. The visual approach uses semantic similarity with multidimensional scaling to collapse high-dimensional phenotype and genotype data from an individual into a graphical format that contextualizes the patient within a low-dimensional disease map. The map proposes a differential diagnosis and algorithmically suggests potential alternatives for phenotype queries--in essence, generating a computationally assisted differential diagnosis informed by the individual's personal genome. Visual interactivity allows the user to filter and update variant rankings by interacting with intermediate results. The tool also implements an adaptive approach for disease gene discovery based on patient phenotypes. RESULTS: We retrospectively analyzed pilot cohort data from the Baylor Miraca Genetics Laboratory, demonstrating performance of the tool and workflow in the re-analysis of clinical exomes. Our tool assigned to clinically reported variants a median rank of 2, placing causal variants in the top 1 % of filtered candidates across the 47 cohort cases with reported molecular diagnoses of exome variants in OMIM Morbidmap genes. Our tool outperformed Phen-Gen, eXtasy, PhenIX, PHIVE, and hiPHIVE in the prioritization of these clinically reported variants. CONCLUSIONS: Our integrative paradigm can improve efficiency and, potentially, the quality of genomic medicine by more effectively utilizing available phenotype information, catalog data, and genomic knowledge.
Keywords: Computational Biology; Diagnosis, Differential; Disease; Genetic Variation; Genome-Wide Association Study; Humans; Phenotype; Pilot Projects; Retrospective Studies; Software

Whole exome sequencing identifies causative mutations in the majority of consanguineous or familial cases with childhood-onset increased renal echogenicity. - Braun, Daniela A; Schueler, Markus; Halbritter, Jan; Gee, Heon Yung; Porath, Jonathan D; Lawson, Jennifer A; Airik, Rannar; Shril, Shirlee; Allen, Susan J; Stein, Deborah; Al Kindy, Adila; Beck, Bodo B; et al. (Kidney Int, 2016)
Chronically increased echogenicity on renal ultrasound is a sensitive early finding of chronic kidney disease that can be detected before manifestation of other symptoms. Increased echogenicity, however, is not specific for a certain etiology of chronic kidney disease. Here, we performed whole exome sequencing in 79 consanguineous or familial cases of suspected nephronophthisis in order to determine the underlying molecular disease cause. In 50 cases, there was a causative mutation in a known monogenic disease gene. In 32 of these cases whole exome sequencing confirmed the diagnosis of a nephronophthisis-related ciliopathy. In 8 cases it revealed the diagnosis of a renal tubulopathy. The remaining 10 cases were identified as Alport syndrome (4), autosomal-recessive polycystic kidney disease (2), congenital anomalies of the kidney and urinary tract (3), and APECED syndrome (1). In 5 families, in whom mutations in known monogenic genes were excluded, we applied homozygosity mapping for variant filtering and identified 5 novel candidate genes (RBM48, FAM186B, PIAS1, INCENP, and RCOR1) for renal ciliopathies. Thus, whole exome sequencing allows the detection of the causative mutation in 2/3 of affected individuals, thereby presenting the etiologic diagnosis, and allows identification of novel candidate genes.
Keywords: Age of Onset; Cohort Studies; DNA Mutational Analysis; Exome; Humans; Kidney Diseases, Cystic; Renal Insufficiency, Chronic

Whole-exome sequencing identifies novel variants in PNPT1 causing oxidative phosphorylation defects and severe multisystem disease. - Alodaib, Ahmad; Sobreira, Nara; Gold, Wendy A; Riley, Lisa G; Van Bergen, Nicole J; Wilson, Meredith J; Bennetts, Bruce; Thorburn, David R; Boehm, Corinne; Christodoulou, John (Eur J Hum Genet, 2016)
Recent advances in next-generation sequencing strategies have led to the discovery of many novel disease genes. We describe here a non-consanguineous family with two affected boys presenting with early onset of severe axonal neuropathy, optic atrophy, intellectual disability, auditory neuropathy and chronic respiratory and gut disturbances. Whole-exome sequencing (WES) was performed on all family members and we identified compound heterozygous variants (c.[760C>A];[1528G>C];p.[(Gln254Lys);(Ala510Pro)] in the polyribonucleotide nucleotidyltransferase 1 (PNPT1) gene in both affected individuals. PNPT1 encodes the polynucleotide phosphorylase (PNPase) protein, which is involved in the transport of small RNAs into the mitochondria. These RNAs are involved in the mitochondrial translation machinery, responsible for the synthesis of mitochondrially encoded subunits of the oxidative phosphorylation (OXPHOS) complexes. Both PNPT1 variants are within highly conserved regions and predicted to be damaging. These variants resulted in quaternary defects in the PNPase protein and a clear reduction in protein and mRNA expression of PNPT1 in patient fibroblasts compared with control cells. Protein analysis of the OXPHOS complexes showed a significant reduction in complex I (CI), complex III (CIII) and complex IV (CIV). Enzyme activity of CI and CIV was clearly reduced in patient fibroblasts compared with controls along with a 33% reduction in total mitochondrial protein synthesis. In vitro rescue experiments, using exogenous expression of wild-type PNPT1 in patient fibroblasts, ameliorated the deficiencies in the OXPHOS complex protein expression, supporting the likely pathogenicity of these variants and the importance of WES in efficiently identifying rare genetic disease genes.
Keywords: Axons; Exome; Exoribonucleases; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Male; Mitochondria; Mutation; Optic Atrophy; Oxidative Phosphorylation; Pedigree; Protein Structure, Quaternary

Whole-Exome Sequencing in Familial Parkinson Disease. - Farlow, Janice L; Robak, Laurie A; Hetrick, Kurt; Bowling, Kevin; Boerwinkle, Eric; Coban-Akdemir, Zeynep H; Gambin, Tomasz; Gibbs, Richard A; Gu, Shen; Jain, Preti; Jankovic, Joseph; Jhangiani, Shalini; et al. (JAMA Neurol, 2016)
IMPORTANCE: Parkinson disease (PD) is a progressive neurodegenerative disease for which susceptibility is linked to genetic and environmental risk factors. OBJECTIVE: To identify genetic variants contributing to disease risk in familial PD. DESIGN, SETTING, AND PARTICIPANTS: A 2-stage study design that included a discovery cohort of families with PD and a replication cohort of familial probands was used. In the discovery cohort, rare exonic variants that segregated in multiple affected individuals in a family and were predicted to be conserved or damaging were retained. Genes with retained variants were prioritized if expressed in the brain and located within PD-relevant pathways. Genes in which prioritized variants were observed in at least 4 families were selected as candidate genes for replication in the replication cohort. The setting was among individuals with familial PD enrolled from academic movement disorder specialty clinics across the United States. All participants had a family history of PD. MAIN OUTCOMES AND MEASURES: Identification of genes containing rare, likely deleterious, genetic variants in individuals with familial PD using a 2-stage exome sequencing study design. RESULTS: The 93 individuals from 32 families in the discovery cohort (49.5% [46 of 93] female) had a mean (SD) age at onset of 61.8 (10.0) years. The 49 individuals with familial PD in the replication cohort (32.6% [16 of 49] female) had a mean (SD) age at onset of 50.1 (15.7) years. Discovery cohort recruitment dates were 1999 to 2009, and replication cohort recruitment dates were 2003 to 2014. Data analysis dates were 2011 to 2015. Three genes containing a total of 13 rare and potentially damaging variants were prioritized in the discovery cohort. Two of these genes (TNK2 and TNR) also had rare variants that were predicted to be damaging in the replication cohort. All 9 variants identified in the 2 replicated genes in 12 families across the discovery and replication cohorts were confirmed via Sanger sequencing. CONCLUSIONS AND RELEVANCE: TNK2 and TNR harbored rare, likely deleterious, variants in individuals having familial PD, with similar findings in an independent cohort. To our knowledge, these genes have not been previously associated with PD, although they have been linked to critical neuronal functions. Further studies are required to confirm a potential role for these genes in the pathogenesis of PD.
Keywords: Adult; Aged; Cohort Studies; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Middle Aged; Parkinsonian Disorders; Protein-Tyrosine Kinases; Sequence Analysis, DNA; Tenascin

Absence of heterozygosity due to template switching during replicative rearrangements. - Carvalho, Claudia M B; Pfundt, Rolph; King, Daniel A; Lindsay, Sarah J; Zuccherato, Luciana W; Macville, Merryn V E; Liu, Pengfei; Johnson, Diana; Stankiewicz, Pawel; Brown, Chester W; Shaw, Chad A; Hurles, Matthew E; et al. (Am J Hum Genet, 2015)
We investigated complex genomic rearrangements (CGRs) consisting of triplication copy-number variants (CNVs) that were accompanied by extended regions of copy-number-neutral absence of heterozygosity (AOH) in subjects with multiple congenital abnormalities. Molecular analyses provided observational evidence that in humans, post-zygotically generated CGRs can lead to regional uniparental disomy (UPD) due to template switches between homologs versus sister chromatids by using microhomology to prime DNA replication-a prediction of the replicative repair model, MMBIR. Our findings suggest that replication-based mechanisms might underlie the formation of diverse types of genomic alterations (CGRs and AOH) implicated in constitutional disorders.
Keywords: Base Sequence; DNA Copy Number Variations; DNA Repair; DNA Replication; Gene Rearrangement; Humans; In Situ Hybridization, Fluorescence; Loss of Heterozygosity; Models, Genetic; Molecular Sequence Data; Netherlands; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Uniparental Disomy

Activating Mutations Affecting the Dbl Homology Domain of SOS2 Cause Noonan Syndrome. - Cordeddu, Viviana; Yin, Jiani C; Gunnarsson, Cecilia; Virtanen, Carl; Drunat, Séverine; Lepri, Francesca; De Luca, Alessandro; Rossi, Cesare; Ciolfi, Andrea; Pugh, Trevor J; Bruselles, Alessandro; Priest, James R; et al. (Hum Mutat, 2015)
The RASopathies constitute a family of autosomal-dominant disorders whose major features include facial dysmorphism, cardiac defects, reduced postnatal growth, variable cognitive deficits, ectodermal and skeletal anomalies, and susceptibility to certain malignancies. Noonan syndrome (NS), the commonest RASopathy, is genetically heterogeneous and caused by functional dysregulation of signal transducers and regulatory proteins with roles in the RAS/extracellular signal-regulated kinase (ERK) signal transduction pathway. Mutations in known disease genes account for approximately 80% of affected individuals. Here, we report that missense mutations altering Son of Sevenless, Drosophila, homolog 2 (SOS2), which encodes a RAS guanine nucleotide exchange factor, occur in a small percentage of subjects with NS. Four missense mutations were identified in five unrelated sporadic cases and families transmitting NS. Disease-causing mutations affected three conserved residues located in the Dbl homology (DH) domain, of which two are directly involved in the intramolecular binding network maintaining SOS2 in its autoinhibited conformation. All mutations were found to promote enhanced signaling from RAS to ERK. Similar to NS-causing SOS1 mutations, the phenotype associated with SOS2 defects is characterized by normal development and growth, as well as marked ectodermal involvement. Unlike SOS1 mutations, however, those in SOS2 are restricted to the DH domain.
Keywords: Adolescent; Adult; Alleles; Amino Acid Substitution; Child; DNA Mutational Analysis; Exome; Facies; Female; Genetic Association Studies; Genotype; Humans; Male; Models, Molecular; Mutation; Noonan Syndrome; Phenotype; Protein Conformation; Protein Interaction Domains and Motifs; Son of Sevenless Proteins; Young Adult

Allelic Mutations of KITLG, Encoding KIT Ligand, Cause Asymmetric and Unilateral Hearing Loss and Waardenburg Syndrome Type 2. - Zazo Seco, Celia; Serrão de Castro, Luciana; van Nierop, Josephine W; Morín, Matías; Jhangiani, Shalini; Verver, Eva J J; Schraders, Margit; Maiwald, Nadine; Wesdorp, Mieke; Venselaar, Hanka; Spruijt, Liesbeth; Oostrik, Jaap; et al. (Am J Hum Genet, 2015)
Linkage analysis combined with whole-exome sequencing in a large family with congenital and stable non-syndromic unilateral and asymmetric hearing loss (NS-UHL/AHL) revealed a heterozygous truncating mutation, c.286_303delinsT (p.Ser96Ter), in KITLG. This mutation co-segregated with NS-UHL/AHL as a dominant trait with reduced penetrance. By screening a panel of probands with NS-UHL/AHL, we found an additional mutation, c.200_202del (p.His67_Cys68delinsArg). In vitro studies revealed that the p.His67_Cys68delinsArg transmembrane isoform of KITLG is not detectable at the cell membrane, supporting pathogenicity. KITLG encodes a ligand for the KIT receptor. Also, KITLG-KIT signaling and MITF are suggested to mutually interact in melanocyte development. Because mutations in MITF are causative of Waardenburg syndrome type 2 (WS2), we screened KITLG in suspected WS2-affected probands. A heterozygous missense mutation, c.310C>G (p.Leu104Val), that segregated with WS2 was identified in a small family. In vitro studies revealed that the p.Leu104Val transmembrane isoform of KITLG is located at the cell membrane, as is wild-type KITLG. However, in culture media of transfected cells, the p.Leu104Val soluble isoform of KITLG was reduced, and no soluble p.His67_Cys68delinsArg and p.Ser96Ter KITLG could be detected. These data suggest that mutations in KITLG associated with NS-UHL/AHL have a loss-of-function effect. We speculate that the mechanism of the mutation underlying WS2 and leading to membrane incorporation and reduced secretion of KITLG occurs via a dominant-negative or gain-of-function effect. Our study unveils different phenotypes associated with KITLG, previously associated with pigmentation abnormalities, and will thereby improve the genetic counseling given to individuals with KITLG variants.
Keywords: Alleles; Animals; Female; Fluorescent Antibody Technique; Genetic Linkage; Hearing Loss, Unilateral; Humans; Male; Mice; Mutation; NIH 3T3 Cells; Pedigree; Phenotype; Prognosis; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Stem Cell Factor; Waardenburg Syndrome

Alu-mediated diverse and complex pathogenic copy-number variants within human chromosome 17 at p13.3. - Gu, Shen; Yuan, Bo; Campbell, Ian M; Beck, Christine R; Carvalho, Claudia M B; Nagamani, Sandesh C S; Erez, Ayelet; Patel, Ankita; Bacino, Carlos A; Shaw, Chad A; Stankiewicz, Paweł; Cheung, Sau Wai; et al. (Hum Mol Genet, 2015)
Alu repetitive elements are known to be major contributors to genome instability by generating Alu-mediated copy-number variants (CNVs). Most of the reported Alu-mediated CNVs are simple deletions and duplications, and the mechanism underlying Alu-Alu-mediated rearrangement has been attributed to non-allelic homologous recombination (NAHR). Chromosome 17 at the p13.3 genomic region lacks extensive low-copy repeat architecture; however, it is highly enriched for Alu repetitive elements, with a fraction of 30% of total sequence annotated in the human reference genome, compared with the 10% genome-wide and 18% on chromosome 17. We conducted mechanistic studies of the 17p13.3 CNVs by performing high-density oligonucleotide array comparative genomic hybridization, specifically interrogating the 17p13.3 region with ∼150 bp per probe density; CNV breakpoint junctions were mapped to nucleotide resolution by polymerase chain reaction and Sanger sequencing. Studied rearrangements include 5 interstitial deletions, 14 tandem duplications, 7 terminal deletions and 13 complex genomic rearrangements (CGRs). Within the 17p13.3 region, Alu-Alu-mediated rearrangements were identified in 80% of the interstitial deletions, 46% of the tandem duplications and 50% of the CGRs, indicating that this mechanism was a major contributor for formation of breakpoint junctions. Our studies suggest that Alu repetitive elements facilitate formation of non-recurrent CNVs, CGRs and other structural aberrations of chromosome 17 at p13.3. The common observation of Alu-mediated rearrangement in CGRs and breakpoint junction sequences analysis further demonstrates that this type of mechanism is unlikely attributed to NAHR, but rather may be due to a recombination-coupled DNA replicative repair process.
Keywords: Alleles; Alu Elements; Base Sequence; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Genome, Human; Genomic Instability; Genomics; Homologous Recombination; Humans; Male; Molecular Sequence Data; Segmental Duplications, Genomic; Sequence Deletion

An anadysplasia-like, spontaneously remitting spondylometaphyseal dysplasia secondary to lamin B receptor (LBR) gene mutations: further definition of the phenotypic heterogeneity of LBR-bone dysplasias. - Sobreira, Nara; Modaff, Peggy; Steel, Gary; You, Jing; Nanda, Sonia; Hoover-Fong, Julie; Valle, David; Pauli, Richard M (Am J Med Genet A, 2015)
We describe a boy who has an anadysplasia-like spondylometaphyseal dysplasia. By whole exome sequencing he was shown to have compound heterozygous mutations of LBR that codes for the lamin B receptor. He shares many similarities with a case previously described, but in whom the early natural history could not be established [Borovik et al., 2013]. Thus, in addition to Greenberg dysplasia (a perinatal lethal disorder), homozygosity or compound heterozygosity of mutations in LBR can result in a mild, spontaneously regressing bone dysplasia.
Keywords: Adolescent; Adult; Child; Child, Preschool; Female; Humans; Infant; Infant, Newborn; Male; Mutation; Osteochondrodysplasias; Phenotype; Pregnancy; Radiography; Receptors, Cytoplasmic and Nuclear; Spine

Assessing structural variation in a personal genome-towards a human reference diploid genome. - English, Adam C; Salerno, William J; Hampton, Oliver A; Gonzaga-Jauregui, Claudia; Ambreth, Shruthi; Ritter, Deborah I; Beck, Christine R; Davis, Caleb F; Dahdouli, Mahmoud; Ma, Singer; Carroll, Andrew; Veeraraghavan, Narayanan; et al. (BMC Genomics, 2015)
BACKGROUND: Characterizing large genomic variants is essential to expanding the research and clinical applications of genome sequencing. While multiple data types and methods are available to detect these structural variants (SVs), they remain less characterized than smaller variants because of SV diversity, complexity, and size. These challenges are exacerbated by the experimental and computational demands of SV analysis. Here, we characterize the SV content of a personal genome with Parliament, a publicly available consensus SV-calling infrastructure that merges multiple data types and SV detection methods. RESULTS: We demonstrate Parliament's efficacy via integrated analyses of data from whole-genome array comparative genomic hybridization, short-read next-generation sequencing, long-read (Pacific BioSciences RSII), long-insert (Illumina Nextera), and whole-genome architecture (BioNano Irys) data from the personal genome of a single subject (HS1011). From this genome, Parliament identified 31,007 genomic loci between 100 bp and 1 Mbp that are inconsistent with the hg19 reference assembly. Of these loci, 9,777 are supported as putative SVs by hybrid local assembly, long-read PacBio data, or multi-source heuristics. These SVs span 59 Mbp of the reference genome (1.8%) and include 3,801 events identified only with long-read data. The HS1011 data and complete Parliament infrastructure, including a BAM-to-SV workflow, are available on the cloud-based service DNAnexus. CONCLUSIONS: HS1011 SV analysis reveals the limits and advantages of multiple sequencing technologies, specifically the impact of long-read SV discovery. With the full Parliament infrastructure, the HS1011 data constitute a public resource for novel SV discovery, software calibration, and personal genome structural variation analysis.
Keywords: Computational Biology; Databases, Genetic; Diploidy; Genome, Human; Genomic Structural Variation; Humans; Sequence Analysis, DNA; Software

Assessment of incidental findings in 232 whole-exome sequences from the Baylor-Hopkins Center for Mendelian Genomics. - Jurgens, Julie; Ling, Hua; Hetrick, Kurt; Pugh, Elizabeth; Schiettecatte, François; Doheny, Kimberly; Hamosh, Ada; Avramopoulos, Dimitri; Valle, David; Sobreira, Nara (Genet Med, 2015)
PURPOSE: In March 2013 the American College of Medical Genetics and Genomics published a list of 56 genes with the recommendation that pathogenic and likely pathogenic variants detected incidentally by clinical sequencing be reported to patients. As an initial step in determining the practical consequences of this recommendation in the research setting, we searched for variants in these genes in 232 whole-exome sequences from the Baylor-Hopkins Center for Mendelian Genomics. METHODS: We identified rare, nonsynonymous, and splicing single-nucleotide variants and insertions/deletions and assessed variant classification using the Human Gene Mutation, Emory, and ClinVar databases. We analyzed the burden of mutation in each of the 56 genes and determined which variants should be reported to patients. RESULTS: Our filtering resulted in 249 distinct variants, with a mean of 1.69 variants per individual. Half of these were novel missense mutations not classified by any of the three reference databases. Of 101 variants listed in the Human Gene Mutation Database, 48 were also in ClinVar and 3 were also in Emory; half of these shared variants were classified discordantly between databases. Some genes consistently had greater variation than others. In total, 0.86% of individuals had a reportable incidental variant. CONCLUSION: These observations demonstrate some current challenges of assessing phenotypic consequences of incidental variants for counseling patients.
Keywords: Databases, Nucleic Acid; Exome; Female; Genetic Diseases, Inborn; Genomics; High-Throughput Nucleotide Sequencing; Humans; Incidental Findings; Male; Mutation; Polymorphism, Single Nucleotide

Association of Rare Loss-Of-Function Alleles in HAL, Serum Histidine: Levels and Incident Coronary Heart Disease. - Yu, Bing; Li, Alexander H; Muzny, Donna; Veeraraghavan, Narayanan; de Vries, Paul S; Bis, Joshua C; Musani, Solomon K; Alexander, Danny; Morrison, Alanna C; Franco, Oscar H; Uitterlinden, André; Hofman, Albert; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Histidine is a semiessential amino acid with antioxidant and anti-inflammatory properties. Few data are available on the associations between genetic variants, histidine levels, and incident coronary heart disease (CHD) in a population-based sample. METHODS AND RESULTS: By conducting whole exome sequencing on 1152 African Americans in the Atherosclerosis Risk in Communities (ARIC) study and focusing on loss-of-function (LoF) variants, we identified 3 novel rare LoF variants in HAL, a gene that encodes histidine ammonia-lyase in the first step of histidine catabolism. These LoF variants had large effects on blood histidine levels (β=0.26; P=1.2×10(-13)). The positive association with histidine levels was replicated by genotyping an independent sample of 718 ARIC African Americans (minor allele frequency=1%; P=1.2×10(-4)). In addition, high blood histidine levels were associated with reduced risk of developing incident CHD with an average of 21.5 years of follow-up among African Americans (hazard ratio=0.18; P=1.9×10(-4)). This finding was validated in an independent sample of European Americans from the Framingham Heart Study (FHS) Offspring Cohort. However, LoF variants in HAL were not directly significantly associated with incident CHD after meta-analyzing results from the CHARGE Consortium. CONCLUSIONS: Three LoF mutations in HAL were associated with increased histidine levels, which in turn were shown to be inversely related to the risk of CHD among both African Americans and European Americans. Future investigations on the association between HAL gene variation and CHD are warranted.
Keywords: Adult; African Americans; Alleles; Coronary Disease; European Continental Ancestry Group; Female; Histidine; Histidine Ammonia-Lyase; Humans; Male; Mutation

Autosomal-Dominant Multiple Pterygium Syndrome Is Caused by Mutations in MYH3. - Chong, Jessica X; Burrage, Lindsay C; Beck, Anita E; Marvin, Colby T; McMillin, Margaret J; Shively, Kathryn M; Harrell, Tanya M; Buckingham, Kati J; Bacino, Carlos A; Jain, Mahim; Alanay, Yasemin; Berry, Susan A; et al. (Am J Hum Genet, 2015)
Multiple pterygium syndrome (MPS) is a phenotypically and genetically heterogeneous group of rare Mendelian conditions characterized by multiple pterygia, scoliosis, and congenital contractures of the limbs. MPS typically segregates as an autosomal-recessive disorder, but rare instances of autosomal-dominant transmission have been reported. Whereas several mutations causing recessive MPS have been identified, the genetic basis of dominant MPS remains unknown. We identified four families affected by dominantly transmitted MPS characterized by pterygia, camptodactyly of the hands, vertebral fusions, and scoliosis. Exome sequencing identified predicted protein-altering mutations in embryonic myosin heavy chain (MYH3) in three families. MYH3 mutations underlie distal arthrogryposis types 1, 2A, and 2B, but all mutations reported to date occur in the head and neck domains. In contrast, two of the mutations found to cause MPS in this study occurred in the tail domain. The phenotypic overlap among persons with MPS, coupled with physical findings distinct from other conditions caused by mutations in MYH3, suggests that the developmental mechanism underlying MPS differs from that of other conditions and/or that certain functions of embryonic myosin might be perturbed by disruption of specific residues and/or domains. Moreover, the vertebral fusions in persons with MPS, coupled with evidence of MYH3 expression in bone, suggest that embryonic myosin plays a role in skeletal development.
Keywords: Arthrogryposis; Cytoskeletal Proteins; Exome; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Mutation; Myosins; Osteogenesis

Biallelic mutations in BRCA1 cause a new Fanconi anemia subtype. - Sawyer, Sarah L; Tian, Lei; Kähkönen, Marketta; Schwartzentruber, Jeremy; Kircher, Martin; Majewski, Jacek; Dyment, David A; Innes, A Micheil; Boycott, Kym M; Moreau, Lisa A; Moilanen, Jukka S; Greenberg, Roger A (Cancer Discov, 2015)
UNLABELLED: Deficiency in BRCA-dependent DNA interstrand crosslink (ICL) repair is intimately connected to breast cancer susceptibility and to the rare developmental syndrome Fanconi anemia. Bona fide Fanconi anemia proteins, BRCA2 (FANCD1), PALB2 (FANCN), and BRIP1 (FANCJ), interact with BRCA1 during ICL repair. However, the lack of detailed phenotypic and cellular characterization of a patient with biallelic BRCA1 mutations has precluded assignment of BRCA1 as a definitive Fanconi anemia susceptibility gene. Here, we report the presence of biallelic BRCA1 mutations in a woman with multiple congenital anomalies consistent with a Fanconi anemia-like disorder and breast cancer at age 23. Patient cells exhibited deficiency in BRCA1 and RAD51 localization to DNA-damage sites, combined with radial chromosome formation and hypersensitivity to ICL-inducing agents. Restoration of these functions was achieved by ectopic introduction of a BRCA1 transgene. These observations provide evidence in support of BRCA1 as a new Fanconi anemia gene (FANCS). SIGNIFICANCE: We establish that biallelic BRCA1 mutations cause a distinct FA-S, which has implications for risk counselling in families where both parents harbor BRCA1 mutations. The genetic basis of hereditary cancer susceptibility syndromes provides diagnostic information, insights into treatment strategies, and more accurate recurrence risk counseling to families.
Keywords: Adult; Alleles; Base Sequence; BRCA1 Protein; Breast Neoplasms; Fanconi Anemia; Fanconi Anemia Complementation Group Proteins; Female; Genes, BRCA1; Genetic Predisposition to Disease; Humans; Mutation; Young Adult

Biallelic mutations in SNX14 cause a syndromic form of cerebellar atrophy and lysosome-autophagosome dysfunction. - Akizu, Naiara; Cantagrel, Vincent; Zaki, Maha S; Al-Gazali, Lihadh; Wang, Xin; Rosti, Rasim Ozgur; Dikoglu, Esra; Gelot, Antoinette Bernabe; Rosti, Basak; Vaux, Keith K; Scott, Eric M; Silhavy, Jennifer L; et al. (Nat Genet, 2015)
Pediatric-onset ataxias often present clinically as developmental delay and intellectual disability, with prominent cerebellar atrophy as a key neuroradiographic finding. Here we describe a new clinically distinguishable recessive syndrome in 12 families with cerebellar atrophy together with ataxia, coarsened facial features and intellectual disability, due to truncating mutations in the sorting nexin gene SNX14, encoding a ubiquitously expressed modular PX domain-containing sorting factor. We found SNX14 localized to lysosomes and associated with phosphatidylinositol (3,5)-bisphosphate, a key component of late endosomes/lysosomes. Patient-derived cells showed engorged lysosomes and a slower autophagosome clearance rate upon autophagy induction by starvation. Zebrafish morphants for snx14 showed dramatic loss of cerebellar parenchyma, accumulation of autophagosomes and activation of apoptosis. Our results characterize a unique ataxia syndrome due to biallelic SNX14 mutations leading to lysosome-autophagosome dysfunction.
Keywords: Animals; Atrophy; Autophagy; Cerebellar Diseases; Cerebellum; Child, Preschool; Female; Gene Frequency; Humans; Infant; Lod Score; Lysosomal Storage Diseases; Lysosomes; Male; Mutation; Phagosomes; Sorting Nexins; Spinocerebellar Ataxias; Syndrome; Zebrafish

Cerebral visual impairment and intellectual disability caused by PGAP1 variants. - Bosch, Daniëlle G M; Boonstra, F Nienke; Kinoshita, Taroh; Jhangiani, Shalini; de Ligt, Joep; Cremers, Frans P M; Lupski, James R; Murakami, Yoshiko; de Vries, Bert B A (Eur J Hum Genet, 2015)
Homozygous variants in PGAP1 (post-GPI attachment to proteins 1) have recently been identified in two families with developmental delay, seizures and/or spasticity. PGAP1 is a member of the glycosylphosphatidylinositol anchor biosynthesis and remodeling pathway and defects in this pathway are a subclass of congenital disorders of glycosylation. Here we performed whole-exome sequencing in an individual with cerebral visual impairment (CVI), intellectual disability (ID), and factor XII deficiency and revealed compound heterozygous variants in PGAP1, c.274_276del (p.(Pro92del)) and c.921_925del (p.(Lys308Asnfs*25)). Subsequently, PGAP1-deficient Chinese hamster ovary (CHO)-cell lines were transfected with either mutant or wild-type constructs and their sensitivity to phosphatidylinositol-specific phospholipase C (PI-PLC) treatment was measured. The mutant constructs could not rescue the PGAP1-deficient CHO cell lines resistance to PI-PLC treatment. In addition, lymphoblastoid cell lines (LCLs) of the affected individual showed no sensitivity to PI-PLC treatment, whereas the LCLs of the heterozygous carrier parents were partially resistant. In conclusion, we report novel PGAP1 variants in a boy with CVI and ID and a proven functional loss of PGAP1 and show, to our knowledge, for the first time this genetic association with CVI.
Keywords: Animals; Cell Line, Tumor; Child; CHO Cells; Cricetinae; Cricetulus; Humans; Intellectual Disability; Male; Membrane Proteins; Mutation; Phosphoinositide Phospholipase C; Phosphoric Monoester Hydrolases; Syndrome; Vision Disorders; Visual Perception

Challenges and solutions for gene identification in the presence of familial locus heterogeneity. - Rehman, Atteeq U; Santos-Cortez, Regie Lyn P; Drummond, Meghan C; Shahzad, Mohsin; Lee, Kwanghyuk; Morell, Robert J; Ansar, Muhammad; Jan, Abid; Wang, Xin; Aziz, Abdul; Riazuddin, Saima; Smith, Joshua D; et al. (Eur J Hum Genet, 2015)
Next-generation sequencing (NGS) of exomes and genomes has accelerated the identification of genes involved in Mendelian phenotypes. However, many NGS studies fall short of identifying causal variants, with estimates for success rates as low as 25% for uncovering the pathological variant underlying disease etiology. An important reason for such failures is familial locus heterogeneity, where within a single pedigree causal variants in two or more genes underlie Mendelian trait etiology. As examples of intra- and inter-sibship familial locus heterogeneity, we present 10 consanguineous Pakistani families segregating hearing impairment due to homozygous variants in two different hearing impairment genes and a European-American pedigree in which hearing impairment is caused by four variants in three different genes. We have identified 41 additional pedigrees with syndromic and nonsyndromic hearing impairment for which a single previously reported hearing impairment gene has been identified but only segregates with the phenotype in a subset of affected pedigree members. We estimate that locus heterogeneity occurs in 15.3% (95% confidence interval: 11.9%, 19.9%) of the families in our collection. We demonstrate novel approaches to apply linkage analysis and homozygosity mapping (for autosomal recessive consanguineous pedigrees), which can be used to detect locus heterogeneity using either NGS or SNP array data. Results from linkage analysis and homozygosity mapping can also be used to group sibships or individuals most likely to be segregating the same causal variants and thereby increase the success rate of gene identification.
Keywords: Asian Continental Ancestry Group; Calcium-Binding Proteins; Chromosome Mapping; Connexin 26; Connexins; Consanguinity; European Continental Ancestry Group; Female; Genes, Recessive; Genetic Heterogeneity; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genotype; Hearing Loss; Hepatocyte Growth Factor; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Membrane Transport Proteins; Mutation; Pedigree; Phenotype; Sulfate Transporters

Characterization of a New DGKE Intronic Mutation in Genetically Unsolved Cases of Familial Atypical Hemolytic Uremic Syndrome. - Mele, Caterina; Lemaire, Mathieu; Iatropoulos, Paraskevas; Piras, Rossella; Bresin, Elena; Bettoni, Serena; Bick, David; Helbling, Daniel; Veith, Regan; Valoti, Elisabetta; Donadelli, Roberta; Murer, Luisa; et al. (Clin J Am Soc Nephrol, 2015)
BACKGROUND AND OBJECTIVES: Genetic and acquired abnormalities causing dysregulation of the complement alternative pathway contribute to atypical hemolytic uremic syndrome (aHUS), a rare disorder characterized by thrombocytopenia, nonimmune microangiopathic hemolytic anemia, and acute kidney failure. However, in a substantial proportion of patients the disease-associated alterations are still unknown. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Whole-exome and whole-genome sequencing were performed in two unrelated families with infantile recessive aHUS. Sequencing of cDNA from affected individuals was used to test for the presence of aberrant mRNA species. Expression of mutant diacylglycerol kinase epsilon (DGKE) protein was evaluated with western blotting. RESULTS: Whole-exome sequencing analysis with conventional variant filtering parameters did not reveal any obvious candidate mutation in the first family. The report of aHUS-associated mutations in DGKE, encoding DGKE, led to re-examination of the noncoding DGKE variants obtained from next-generation sequencing, allowing identification of a novel intronic DGKE mutation (c.888+40A>G) that segregated with disease. Sequencing of cDNA from affected individuals revealed aberrant forms of DGKE mRNA predicted to cause profound abnormalities in the protein catalytic site. By whole-genome sequencing, the same mutation was found in compound heterozygosity with a second nonsense DGKE mutation in all affected siblings of another unrelated family. Homozygous and compound heterozygous patients presented similar clinical features, including aHUS presentation in the first year of life, multiple relapsing episodes, and proteinuria, which are prototypical of DGKE-associated aHUS. CONCLUSIONS: This is the first report of a mutation located beyond the exon-intron boundaries in aHUS. Intronic mutations such as these are underreported because conventional filtering parameters used to process next-generation sequencing data routinely exclude these regions from downstream analyses in both research and clinical settings. The results suggest that analysis of noncoding regions of aHUS-associated genes coupled with mRNA sequencing might provide a tool to explain genetically unsolved aHUS cases.
Keywords: Adolescent; Atypical Hemolytic Uremic Syndrome; Base Sequence; Blotting, Western; Child; Diacylglycerol Kinase; DNA Mutational Analysis; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heterozygote; Homozygote; Humans; Infant; Introns; Male; Molecular Sequence Data; Mutation; Phenotype; Predictive Value of Tests; Risk Factors

CNV instability associated with DNA replication dynamics: evidence for replicative mechanisms in CNV mutagenesis. - Chen, Lu; Zhou, Weichen; Zhang, Cheng; Lupski, James R; Jin, Li; Zhang, Feng (Hum Mol Genet, 2015)
Copy number variation (CNV) in the human genome is of vital importance to human health and evolution of our species. However, much of the molecular basis of CNV mutagenesis remains to be elucidated. Considering the DNA replication model of 'fork stalling and template switching' for CNV formation, we hypothesized that replication fork progression could be important for CNV mutagenesis. However, molecular assays of replication fork progression at the genome level are technically challenging. Instead, we conducted an estimation of DNA replication dynamics, as the statistic R, using the readily available data of replication timing. Small R-values can reflect 'slowed' replication, which could result from less fork initiation, reduced fork speed or fork barriers. We generated genome-wide profiles of R in the genomes of human, mouse and Drosophila. Intriguingly, the CNV breakpoints in all three genomes showed significantly biased distributions toward the genomic regions with small R-values, suggesting potential replication stress-induced CNV instability. Notably, among the human CNVs with distinct breakpoint junction characteristics, the homology-mediated and VNTR-mediated CNVs contribute the most to the correlation between CNV instability and the statistic R, consistent with the recent findings in the C. elegans and yeast genomes of repeat-induced DNA replication error and consequent CNV formation. The statistic R may reflect both replication stress and the effect of local genome architecture on fork progression. Our concordant observations suggest an important role for DNA replicative mechanisms in CNV mutagenesis and genome instability.
Keywords: Animals; DNA Copy Number Variations; DNA Replication; Drosophila; Genome; Genomic Instability; Humans; Mice

Cognitive phenotypes and genomic copy number variations. - Lupski, James R (JAMA, 2015)
Keywords: DNA Copy Number Variations; Female; Heterozygote; Humans; Intellectual Disability; Male; Mental Disorders

Collapsed haplotype pattern method for linkage analysis of next-generation sequence data. - Wang, Gao T; Zhang, Di; Li, Biao; Dai, Hang; Leal, Suzanne M (Eur J Hum Genet, 2015)
Recent advances in next-generation sequencing (NGS) make it possible to directly sequence genomes and exomes of individuals with Mendelian diseases and screen sequence data for causal variants. With the reduction in cost of NGS, DNA samples from entire families can be sequenced and linkage analysis can be performed directly using NGS data. Inspired by 'burden' tests, which are used for complex trait rare variant association studies, we developed the collapsed haplotype pattern (CHP) method for linkage analysis. Using data from several deafness genes we demonstrate that the CHP method is substantially more powerful than analyzing individual variants. Unlike applying NGS data filtering approaches, the CHP method provides statistical evidence of a gene's involvement in disease etiology and is also less likely to exclude causal variants in the presence of phenocopies and/or reduced penetrance. The CHP method was implemented in the SEQLinkage software package, which can perform linkage analysis on NGS data or can generate data compatible with many linkage analysis programs, reviving them for use in NGS era.
Keywords: Chromosome Mapping; Genetic Linkage; Haplotypes; Hearing Loss; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Software

Comparative Genomic Analyses of the Human NPHP1 Locus Reveal Complex Genomic Architecture and Its Regional Evolution in Primates. - Yuan, Bo; Liu, Pengfei; Gupta, Aditya; Beck, Christine R; Tejomurtula, Anusha; Campbell, Ian M; Gambin, Tomasz; Simmons, Alexandra D; Withers, Marjorie A; Harris, R Alan; Rogers, Jeffrey; Schwartz, David C; et al. (PLoS Genet, 2015)
Many loci in the human genome harbor complex genomic structures that can result in susceptibility to genomic rearrangements leading to various genomic disorders. Nephronophthisis 1 (NPHP1, MIM# 256100) is an autosomal recessive disorder that can be caused by defects of NPHP1; the gene maps within the human 2q13 region where low copy repeats (LCRs) are abundant. Loss of function of NPHP1 is responsible for approximately 85% of the NPHP1 cases-about 80% of such individuals carry a large recurrent homozygous NPHP1 deletion that occurs via nonallelic homologous recombination (NAHR) between two flanking directly oriented ~45 kb LCRs. Published data revealed a non-pathogenic inversion polymorphism involving the NPHP1 gene flanked by two inverted ~358 kb LCRs. Using optical mapping and array-comparative genomic hybridization, we identified three potential novel structural variant (SV) haplotypes at the NPHP1 locus that may protect a haploid genome from the NPHP1 deletion. Inter-species comparative genomic analyses among primate genomes revealed massive genomic changes during evolution. The aggregated data suggest that dynamic genomic rearrangements occurred historically within the NPHP1 locus and generated SV haplotypes observed in the human population today, which may confer differential susceptibility to genomic instability and the NPHP1 deletion within a personal genome. Our study documents diverse SV haplotypes at a complex LCR-laden human genomic region. Comparative analyses provide a model for how this complex region arose during primate evolution, and studies among humans suggest that intra-species polymorphism may potentially modulate an individual's susceptibility to acquiring disease-associated alleles.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Comparative Genomic Hybridization; Evolution, Molecular; Gene Dosage; Gene Rearrangement; Genome, Human; Genomic Structural Variation; Haplotypes; Humans; Kidney Diseases, Cystic; Membrane Proteins; Primates

Complex genomic rearrangements at the PLP1 locus include triplication and quadruplication. - Beck, Christine R; Carvalho, Claudia M B; Banser, Linda; Gambin, Tomasz; Stubbolo, Danielle; Yuan, Bo; Sperle, Karen; McCahan, Suzanne M; Henneke, Marco; Seeman, Pavel; Garbern, James Y; Hobson, Grace M; et al. (PLoS Genet, 2015)
Inverted repeats (IRs) can facilitate structural variation as crucibles of genomic rearrangement. Complex duplication-inverted triplication-duplication (DUP-TRP/INV-DUP) rearrangements that contain breakpoint junctions within IRs have been recently associated with both MECP2 duplication syndrome (MIM#300260) and Pelizaeus-Merzbacher disease (PMD, MIM#312080). We investigated 17 unrelated PMD subjects with copy number gains at the PLP1 locus including triplication and quadruplication of specific genomic intervals-16/17 were found to have a DUP-TRP/INV-DUP rearrangement product. An IR distal to PLP1 facilitates DUP-TRP/INV-DUP formation as well as an inversion structural variation found frequently amongst normal individuals. We show that a homology-or homeology-driven replicative mechanism of DNA repair can apparently mediate template switches within stretches of microhomology. Moreover, we provide evidence that quadruplication and potentially higher order amplification of a genomic interval can occur in a manner consistent with rolling circle amplification as predicted by the microhomology-mediated break induced replication (MMBIR) model.
Keywords: Chromosome Breakpoints; Chromosome Inversion; Gene Dosage; Gene Duplication; Humans; Myelin Proteolipid Protein; Pelizaeus-Merzbacher Disease

Continued lessons from the INS gene: an intronic mutation causing diabetes through a novel mechanism. - Carmody, David; Park, Soo-Young; Ye, Honggang; Perrone, Marie E; Alkorta-Aranburu, G; Highland, Heather M; Hanis, Craig L; Philipson, Louis H; Bell, Graeme I; Greeley, Siri Atma W (J Med Genet, 2015)
BACKGROUND: Diabetes in neonates usually has a monogenic aetiology; however, the cause remains unknown in 20-30%. Heterozygous INS mutations represent one of the most common gene causes of neonatal diabetes mellitus. METHODS: Clinical and functional characterisation of a novel homozygous intronic mutation (c.187+241G>A) in the insulin gene in a child identified through the Monogenic Diabetes Registry (http://monogenicdiabetes.uchicago.edu). RESULTS: The proband had insulin-requiring diabetes from birth. Ultrasonography revealed a structurally normal pancreas and C-peptide was undetectable despite readily detectable amylin, suggesting the presence of dysfunctional β cells. Whole-exome sequencing revealed the novel mutation. In silico analysis predicted a mutant mRNA product resulting from preferential recognition of a newly created splice site. Wild-type and mutant human insulin gene constructs were derived and transiently expressed in INS-1 cells. We confirmed the predicted transcript and found an additional transcript created via an ectopic splice acceptor site. CONCLUSIONS: Dominant INS mutations cause diabetes via a mutated translational product causing endoplasmic reticulum stress. We describe a novel mechanism of diabetes, without β cell death, due to creation of two unstable mutant transcripts predicted to undergo nonsense and non-stop-mediated decay, respectively. Our discovery may have broader implications for those with insulin deficiency later in life.
Keywords: Diabetes Mellitus; Humans; Infant; Insulin, Regular, Human; Introns; Mutation; Sequence Analysis, DNA

COPA mutations impair ER-Golgi transport and cause hereditary autoimmune-mediated lung disease and arthritis. - Watkin, Levi B; Jessen, Birthe; Wiszniewski, Wojciech; Vece, Timothy J; Jan, Max; Sha, Youbao; Thamsen, Maike; Santos-Cortez, Regie L P; Lee, Kwanghyuk; Gambin, Tomasz; Forbes, Lisa R; Law, Christopher S; et al. (Nat Genet, 2015)
Unbiased genetic studies have uncovered surprising molecular mechanisms in human cellular immunity and autoimmunity. We performed whole-exome sequencing and targeted sequencing in five families with an apparent mendelian syndrome of autoimmunity characterized by high-titer autoantibodies, inflammatory arthritis and interstitial lung disease. We identified four unique deleterious variants in the COPA gene (encoding coatomer subunit α) affecting the same functional domain. Hypothesizing that mutant COPA leads to defective intracellular transport via coat protein complex I (COPI), we show that COPA variants impair binding to proteins targeted for retrograde Golgi-to-ER transport. Additionally, expression of mutant COPA results in ER stress and the upregulation of cytokines priming for a T helper type 17 (TH17) response. Patient-derived CD4(+) T cells also demonstrate significant skewing toward a TH17 phenotype that is implicated in autoimmunity. Our findings uncover an unexpected molecular link between a vesicular transport protein and a syndrome of autoimmunity manifested by lung and joint disease.
Keywords: Amino Acid Sequence; Arthritis; Autoimmune Diseases; Child, Preschool; Coatomer Protein; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Female; Genetic Association Studies; Genetic Predisposition to Disease; Golgi Apparatus; HEK293 Cells; Humans; Infant; Lod Score; Lung Diseases, Interstitial; Male; Molecular Sequence Data; Pedigree; Protein Transport

CRB1-Related Maculopathy With Cystoid Macular Edema. - Wolfson, Yulia; Applegate, Carolyn D; Strauss, Rupert W; Han, Ian C; Scholl, Hendrik P (JAMA Ophthalmol, 2015)
Keywords: Administration, Topical; Carbonic Anhydrase Inhibitors; Child; Diseases in Twins; DNA Mutational Analysis; Electroretinography; Eye Proteins; Female; Fluorescein Angiography; Humans; Macular Edema; Membrane Proteins; Mutation; Nerve Tissue Proteins; Ophthalmic Solutions; Retinal Dystrophies; Sulfonamides; Thiophenes; Tomography, Optical Coherence; Twins, Monozygotic; Visual Acuity

De Novo GMNN Mutations Cause Autosomal-Dominant Primordial Dwarfism Associated with Meier-Gorlin Syndrome. - Burrage, Lindsay C; Charng, Wu-Lin; Eldomery, Mohammad K; Willer, Jason R; Davis, Erica E; Lugtenberg, Dorien; Zhu, Wenmiao; Leduc, Magalie S; Akdemir, Zeynep C; Azamian, Mahshid; Zapata, Gladys; Hernandez, Patricia P; et al. (Am J Hum Genet, 2015)
Meier-Gorlin syndrome (MGS) is a genetically heterogeneous primordial dwarfism syndrome known to be caused by biallelic loss-of-function mutations in one of five genes encoding pre-replication complex proteins: ORC1, ORC4, ORC6, CDT1, and CDC6. Mutations in these genes cause disruption of the origin of DNA replication initiation. To date, only an autosomal-recessive inheritance pattern has been described in individuals with this disorder, with a molecular etiology established in about three-fourths of cases. Here, we report three subjects with MGS and de novo heterozygous mutations in the 5' end of GMNN, encoding the DNA replication inhibitor geminin. We identified two truncating mutations in exon 2 (the 1(st) coding exon), c.16A>T (p.Lys6(∗)) and c.35_38delTCAA (p.Ile12Lysfs(∗)4), and one missense mutation, c.50A>G (p.Lys17Arg), affecting the second-to-last nucleotide of exon 2 and possibly RNA splicing. Geminin is present during the S, G2, and M phases of the cell cycle and is degraded during the metaphase-anaphase transition by the anaphase-promoting complex (APC), which recognizes the destruction box sequence near the 5' end of the geminin protein. All three GMNN mutations identified alter sites 5' to residue Met28 of the protein, which is located within the destruction box. We present data supporting a gain-of-function mechanism, in which the GMNN mutations result in proteins lacking the destruction box and hence increased protein stability and prolonged inhibition of replication leading to autosomal-dominant MGS.
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Cell Cycle; Child, Preschool; Congenital Microtia; Dwarfism; Exons; Female; Geminin; Gene Expression; Genes, Dominant; Growth Disorders; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Micrognathism; Molecular Sequence Data; Mutation; Patella; Pedigree; Protein Stability; Proteolysis; RNA Splicing; Sequence Alignment

De novo mutations in NALCN cause a syndrome characterized by congenital contractures of the limbs and face, hypotonia, and developmental delay. - Chong, Jessica X; McMillin, Margaret J; Shively, Kathryn M; Beck, Anita E; Marvin, Colby T; Armenteros, Jose R; Buckingham, Kati J; Nkinsi, Naomi T; Boyle, Evan A; Berry, Margaret N; Bocian, Maureen; Foulds, Nicola; et al. (Am J Hum Genet, 2015)
Freeman-Sheldon syndrome, or distal arthrogryposis type 2A (DA2A), is an autosomal-dominant condition caused by mutations in MYH3 and characterized by multiple congenital contractures of the face and limbs and normal cognitive development. We identified a subset of five individuals who had been putatively diagnosed with "DA2A with severe neurological abnormalities" and for whom congenital contractures of the limbs and face, hypotonia, and global developmental delay had resulted in early death in three cases; this is a unique condition that we now refer to as CLIFAHDD syndrome. Exome sequencing identified missense mutations in the sodium leak channel, non-selective (NALCN) in four families affected by CLIFAHDD syndrome. We used molecular-inversion probes to screen for NALCN in a cohort of 202 distal arthrogryposis (DA)-affected individuals as well as concurrent exome sequencing of six other DA-affected individuals, thus revealing NALCN mutations in ten additional families with "atypical" forms of DA. All 14 mutations were missense variants predicted to alter amino acid residues in or near the S5 and S6 pore-forming segments of NALCN, highlighting the functional importance of these segments. In vitro functional studies demonstrated that NALCN alterations nearly abolished the expression of wild-type NALCN, suggesting that alterations that cause CLIFAHDD syndrome have a dominant-negative effect. In contrast, homozygosity for mutations in other regions of NALCN has been reported in three families affected by an autosomal-recessive condition characterized mainly by hypotonia and severe intellectual disability. Accordingly, mutations in NALCN can cause either a recessive or dominant condition characterized by varied though overlapping phenotypic features, perhaps based on the type of mutation and affected protein domain(s).
Keywords: Arthrogryposis; Contracture; Craniofacial Dysostosis; Cytoskeletal Proteins; Exome; Extremities; Face; Female; Gene Frequency; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant; Male; Muscle Hypotonia; Mutation, Missense; Sodium Channels

DNA REPAIR. Mus81 and converging forks limit the mutagenicity of replication fork breakage. - Mayle, Ryan; Campbell, Ian M; Beck, Christine R; Yu, Yang; Wilson, Marenda; Shaw, Chad A; Bjergbaek, Lotte; Lupski, James R; Ira, Grzegorz (Science, 2015)
Most spontaneous DNA double-strand breaks (DSBs) result from replication-fork breakage. Break-induced replication (BIR), a genome rearrangement-prone repair mechanism that requires the Pol32/POLD3 subunit of eukaryotic DNA Polδ, was proposed to repair broken forks, but how genome destabilization is avoided was unknown. We show that broken fork repair initially uses error-prone Pol32-dependent synthesis, but that mutagenic synthesis is limited to within a few kilobases from the break by Mus81 endonuclease and a converging fork. Mus81 suppresses template switches between both homologous sequences and diverged human Alu repetitive elements, highlighting its importance for stability of highly repetitive genomes. We propose that lack of a timely converging fork or Mus81 may propel genome instability observed in cancer.
Keywords: Alu Elements; Base Sequence; DNA Breaks, Double-Stranded; DNA Repair; DNA Replication; DNA-Binding Proteins; DNA-Directed DNA Polymerase; Endonucleases; Genomic Instability; Humans; Molecular Sequence Data; Neoplasms; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins

Dominant De Novo Mutations in GJA1 Cause Erythrokeratodermia Variabilis et Progressiva, without Features of Oculodentodigital Dysplasia. - Boyden, Lynn M; Craiglow, Brittany G; Zhou, Jing; Hu, Ronghua; Loring, Erin C; Morel, Kimberly D; Lauren, Christine T; Lifton, Richard P; Bilguvar, Kaya; Paller, Amy S; Choate, Keith A (J Invest Dermatol, 2015)
Genetic investigation of inherited skin disorders has informed the understanding of skin self-renewal, differentiation, and barrier function. Erythrokeratodermia variabilis et progressiva (EKVP) is a rare, inherited skin disease that is characterized by transient figurate patches of erythema, localized or generalized scaling, and frequent palmoplantar keratoderma. By using exome sequencing, we show that de novo missense mutations in GJA1 (gap junction protein alpha 1) cause EKVP. The severe, progressive skin disease in EKVP subjects with GJA1 mutations is distinct from limited cutaneous findings rarely found in the systemic disorder oculodentodigital dysplasia, also caused by dominant GJA1 mutations. GJA1 encodes connexin 43 (Cx43), the most widely expressed gap junction protein. We show that the GJA1 mutations in EKVP subjects lead to disruption of Cx43 membrane localization and aggregation within the Golgi. These findings reveal a critical role for Cx43 in epidermal homeostasis, and they provide evidence of organ-specific pathobiology resulting from different mutations within GJA1.
Keywords: Amino Acid Sequence; Cell Membrane; Child; Child, Preschool; Connexin 43; Connexins; Craniofacial Abnormalities; Disease Progression; Erythrokeratodermia Variabilis; Exome; Eye Abnormalities; Female; Foot Deformities, Congenital; Golgi Apparatus; HeLa Cells; Humans; Immunohistochemistry; Male; Molecular Sequence Data; Mutagenesis, Site-Directed; Mutation; Phenotype; Sequence Analysis, DNA; Sequence Homology, Amino Acid; Skin Diseases; Syndactyly; Tooth Abnormalities

DVL1 frameshift mutations clustering in the penultimate exon cause autosomal-dominant Robinow syndrome. - White, Janson; Mazzeu, Juliana F; Hoischen, Alexander; Jhangiani, Shalini N; Gambin, Tomasz; Alcino, Michele Calijorne; Penney, Samantha; Saraiva, Jorge M; Hove, Hanne; Skovby, Flemming; Kayserili, Hülya; Estrella, Elicia; et al. (Am J Hum Genet, 2015)
Robinow syndrome is a genetically heterogeneous disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features and for which both autosomal-recessive and autosomal-dominant inheritance patterns have been described. Causative variants in the non-canonical signaling gene WNT5A underlie a subset of autosomal-dominant Robinow syndrome (DRS) cases, but most individuals with DRS remain without a molecular diagnosis. We performed whole-exome sequencing in four unrelated DRS-affected individuals without coding mutations in WNT5A and found heterozygous DVL1 exon 14 mutations in three of them. Targeted Sanger sequencing in additional subjects with DRS uncovered DVL1 exon 14 mutations in five individuals, including a pair of monozygotic twins. In total, six distinct frameshift mutations were found in eight subjects, and all were heterozygous truncating variants within the penultimate exon of DVL1. In five families in which samples from unaffected parents were available, the variants were demonstrated to represent de novo mutations. All variant alleles are predicted to result in a premature termination codon within the last exon, escape nonsense-mediated decay (NMD), and most likely generate a C-terminally truncated protein with a distinct -1 reading-frame terminus. Study of the transcripts extracted from affected subjects' leukocytes confirmed expression of both wild-type and variant alleles, supporting the hypothesis that mutant mRNA escapes NMD. Genomic variants identified in our study suggest that truncation of the C-terminal domain of DVL1, a protein hypothesized to have a downstream role in the Wnt-5a non-canonical pathway, is a common cause of DRS.
Keywords: Adaptor Proteins, Signal Transducing; Amino Acid Sequence; Base Sequence; Craniofacial Abnormalities; Dishevelled Proteins; DNA Primers; Dwarfism; Exome; Exons; Frameshift Mutation; Gene Components; Humans; Limb Deformities, Congenital; Molecular Sequence Data; Phosphoproteins; Sequence Analysis, DNA; Urogenital Abnormalities

Early-onset lymphoproliferation and autoimmunity caused by germline STAT3 gain-of-function mutations. - Milner, Joshua D; Vogel, Tiphanie P; Forbes, Lisa; Ma, Chi A; Stray-Pedersen, Asbjørg; Niemela, Julie E; Lyons, Jonathan J; Engelhardt, Karin R; Zhang, Yu; Topcagic, Nermina; Roberson, Elisha D O; Matthews, Helen; et al. (Blood, 2015)
Germline loss-of-function mutations in the transcription factor signal transducer and activator of transcription 3 (STAT3) cause immunodeficiency, whereas somatic gain-of-function mutations in STAT3 are associated with large granular lymphocytic leukemic, myelodysplastic syndrome, and aplastic anemia. Recently, germline mutations in STAT3 have also been associated with autoimmune disease. Here, we report on 13 individuals from 10 families with lymphoproliferation and early-onset solid-organ autoimmunity associated with 9 different germline heterozygous mutations in STAT3. Patients exhibited a variety of clinical features, with most having lymphadenopathy, autoimmune cytopenias, multiorgan autoimmunity (lung, gastrointestinal, hepatic, and/or endocrine dysfunction), infections, and short stature. Functional analyses demonstrate that these mutations confer a gain-of-function in STAT3 leading to secondary defects in STAT5 and STAT1 phosphorylation and the regulatory T-cell compartment. Treatment targeting a cytokine pathway that signals through STAT3 led to clinical improvement in 1 patient, suggesting a potential therapeutic option for such patients. These results suggest that there is a broad range of autoimmunity caused by germline STAT3 gain-of-function mutations, and that hematologic autoimmunity is a major component of this newly described disorder. Some patients for this study were enrolled in a trial registered at www.clinicaltrials.gov as #NCT00001350.
Keywords: Adolescent; Adult; Autoimmune Diseases; Child; Child, Preschool; Female; Genetic Diseases, Inborn; Humans; Infant; Lymphoproliferative Disorders; Male; Mutation; Phosphorylation; STAT1 Transcription Factor; STAT3 Transcription Factor; STAT5 Transcription Factor; T-Lymphocytes, Regulatory

Exome analysis of a family with Wolff-Parkinson-White syndrome identifies a novel disease locus. - Bowles, Neil E; Jou, Chuanchau J; Arrington, Cammon B; Kennedy, Brett J; Earl, Aubree; Matsunami, Norisada; Meyers, Lindsay L; Etheridge, Susan P; Saarel, Elizabeth V; Bleyl, Steven B; Yost, H Joseph; Yandell, Mark; et al. (Am J Med Genet A, 2015)
Wolff-Parkinson-White (WPW) syndrome is a common cause of supraventricular tachycardia that carries a risk of sudden cardiac death. To date, mutations in only one gene, PRKAG2, which encodes the 5'-AMP-activated protein kinase subunit γ-2, have been identified as causative for WPW. DNA samples from five members of a family with WPW were analyzed by exome sequencing. We applied recently designed prioritization strategies (VAAST/pedigree VAAST) coupled with an ontology-based algorithm (Phevor) that reduced the number of potentially damaging variants to 10: a variant in KCNE2 previously associated with Long QT syndrome was also identified. Of these 11 variants, only MYH6 p.E1885K segregated with the WPW phenotype in all affected individuals and was absent in 10 unaffected family members. This variant was predicted to be damaging by in silico methods and is not present in the 1,000 genome and NHLBI exome sequencing project databases. Screening of a replication cohort of 47 unrelated WPW patients did not identify other likely causative variants in PRKAG2 or MYH6. MYH6 variants have been identified in patients with atrial septal defects, cardiomyopathies, and sick sinus syndrome. Our data highlight the pleiotropic nature of phenotypes associated with defects in this gene.
Keywords: Adult; AMP-Activated Protein Kinases; Cardiac Myosins; Exome; Female; Genetic Loci; Humans; Male; Myosin Heavy Chains; Pedigree; Potassium Channels, Voltage-Gated; Wolff-Parkinson-White Syndrome

Exome Sequence Analysis Suggests that Genetic Burden Contributes to Phenotypic Variability and Complex Neuropathy. - Gonzaga-Jauregui, Claudia; Harel, Tamar; Gambin, Tomasz; Kousi, Maria; Griffin, Laurie B; Francescatto, Ludmila; Ozes, Burcak; Karaca, Ender; Jhangiani, Shalini N; Bainbridge, Matthew N; Lawson, Kim S; Pehlivan, Davut; et al. (Cell Rep, 2015)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous distal symmetric polyneuropathy. Whole-exome sequencing (WES) of 40 individuals from 37 unrelated families with CMT-like peripheral neuropathy refractory to molecular diagnosis identified apparent causal mutations in ∼ 45% (17/37) of families. Three candidate disease genes are proposed, supported by a combination of genetic and in vivo studies. Aggregate analysis of mutation data revealed a significantly increased number of rare variants across 58 neuropathy-associated genes in subjects versus controls, confirmed in a second ethnically discrete neuropathy cohort, suggesting that mutation burden potentially contributes to phenotypic variability. Neuropathy genes shown to have highly penetrant Mendelizing variants (HPMVs) and implicated by burden in families were shown to interact genetically in a zebrafish assay exacerbating the phenotype established by the suppression of single genes. Our findings suggest that the combinatorial effect of rare variants contributes to disease burden and variable expressivity.
Keywords: Animals; Charcot-Marie-Tooth Disease; Exome; Female; Genetic Load; Genetic Variation; HSP40 Heat-Shock Proteins; Humans; Male; Mutation; Myelin P2 Protein; Pedigree; Penetrance; Peripheral Nervous System Diseases; Phenotype; Serine C-Palmitoyltransferase; Suppression, Genetic; Zebrafish

Exome sequencing identifies a homozygous C5orf42 variant in a Turkish kindred with oral-facial-digital syndrome type VI. - Bayram, Yavuz; Aydin, Hatip; Gambin, Tomasz; Akdemir, Zeynep Coban; Atik, Mehmed M; Karaca, Ender; Karaman, Ali; Pehlivan, Davut; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Am J Med Genet A, 2015)
Oral-facial-digital syndrome type VI (OFDVI) is a rare ciliopathy in the spectrum of Joubert syndrome (JS) and distinguished from other oral-facial-digital syndromes by metacarpal abnormalities with central polydactyly and by a molar tooth sign on cranial MRI. Additional characteristic features include short stature, micrognathia, posteriorly rotated low-set ears, hypertelorism, epicanthal folds, broad nasal tip, tongue hamartoma, upper lip notch, intraoral frenula, cleft lip/palate, and renal anomalies. Recently, novel mutations in C5orf42 were identified in 9 out of 11 OFDVI families. In a subsequent study C5orf42 was found to be mutated in only 2 out of 17 OFDVI probands while 28 patients with a pure JS phenotype also had pathogenic mutations of C5orf42. We report on two affected cousins diagnosed with OFDVI who were born from first degree cousin marriages. Whole exome sequencing (WES) identified a homozygous predicted damaging missense mutation (c.4034A > G; p.Gln1345Arg) in the C5orf42 gene. Our data contribute to the evidence that C5orf42 is one of the causative genes for OFDVI.
Keywords: Abnormalities, Multiple; Cerebellar Diseases; Cerebellum; Child; Cleft Palate; Exome; Eye Abnormalities; Female; Genetic Predisposition to Disease; Hamartoma; Homozygote; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Male; Membrane Proteins; Middle Aged; Mutation; Orofaciodigital Syndromes; Phenotype; Retina; Turkey

Exome sequencing links mutations in PARN and RTEL1 with familial pulmonary fibrosis and telomere shortening. - Stuart, Bridget D; Choi, Jungmin; Zaidi, Samir; Xing, Chao; Holohan, Brody; Chen, Rui; Choi, Mihwa; Dharwadkar, Pooja; Torres, Fernando; Girod, Carlos E; Weissler, Jonathan; Fitzgerald, John; et al. (Nat Genet, 2015)
Idiopathic pulmonary fibrosis (IPF) is an age-related disease featuring progressive lung scarring. To elucidate the molecular basis of IPF, we performed exome sequencing of familial kindreds with pulmonary fibrosis. Gene burden analysis comparing 78 European cases and 2,816 controls implicated PARN, an exoribonuclease with no previous connection to telomere biology or disease, with five new heterozygous damaging mutations in unrelated cases and none in controls (P = 1.3 × 10(-8)); mutations were shared by all affected relatives (odds in favor of linkage = 4,096:1). RTEL1, an established locus for dyskeratosis congenita, harbored significantly more new damaging and missense variants at conserved residues in cases than in controls (P = 1.6 × 10(-6)). PARN and RTEL1 mutation carriers had shortened leukocyte telomere lengths, and we observed epigenetic inheritance of short telomeres in family members. Together, these genes explain ~7% of familial pulmonary fibrosis and strengthen the link between lung fibrosis and telomere dysfunction.
Keywords: Adult; Aged; Aged, 80 and over; Amino Acid Sequence; Case-Control Studies; Cells, Cultured; DNA Helicases; DNA Mutational Analysis; Exome; Exoribonucleases; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Idiopathic Pulmonary Fibrosis; Leukocytes; Lod Score; Male; Middle Aged; Molecular Sequence Data; Pedigree; Telomere; Telomere Shortening

Exome sequencing reveals homozygous TRIM2 mutation in a patient with early onset CMT and bilateral vocal cord paralysis. - Pehlivan, Davut; Coban Akdemir, Zeynep; Karaca, Ender; Bayram, Yavuz; Jhangiani, Shalini; Yildiz, Edibe Pembegul; Muzny, Donna; Uluc, Kayihan; Gibbs, Richard A; Elcioglu, Nursel; Lupski, James R; Harel, Tamar (Hum Genet, 2015)
Charcot-Marie-Tooth disease is a heterogeneous group of inherited distal symmetric polyneuropathies associated with mutations in genes encoding components essential for normal functioning of the Schwann cell and axon. TRIM2, encoding a ligase that ubiquitinates the neurofilament light chain, was recently associated with early-onset neuropathy in a single patient. We report a TRIM2 homozygous missense mutation (c.2000A>C; p.D667A) in a patient with peripheral neuropathy and bilateral vocal cord paralysis, allowing for further delineation of the associated phenotypic spectrum.
Keywords: Adult; Charcot-Marie-Tooth Disease; Exome; Female; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant, Newborn; Male; Mutation, Missense; Nuclear Proteins; Vocal Cord Paralysis

Exome sequencing reveals pathogenic mutations in 91 strains of mice with Mendelian disorders. - Fairfield, Heather; Srivastava, Anuj; Ananda, Guruprasad; Liu, Rangjiao; Kircher, Martin; Lakshminarayana, Anuradha; Harris, Belinda S; Karst, Son Yong; Dionne, Louise A; Kane, Coleen C; Curtain, Michelle; Berry, Melissa L; et al. (Genome Res, 2015)
Spontaneously arising mouse mutations have served as the foundation for understanding gene function for more than 100 years. We have used exome sequencing in an effort to identify the causative mutations for 172 distinct, spontaneously arising mouse models of Mendelian disorders, including a broad range of clinically relevant phenotypes. To analyze the resulting data, we developed an analytics pipeline that is optimized for mouse exome data and a variation database that allows for reproducible, user-defined data mining as well as nomination of mutation candidates through knowledge-based integration of sample and variant data. Using these new tools, putative pathogenic mutations were identified for 91 (53%) of the strains in our study. Despite the increased power offered by potentially unlimited pedigrees and controlled breeding, about half of our exome cases remained unsolved. Using a combination of manual analyses of exome alignments and whole-genome sequencing, we provide evidence that a large fraction of unsolved exome cases have underlying structural mutations. This result directly informs efforts to investigate the similar proportion of apparently Mendelian human phenotypes that are recalcitrant to exome sequencing.
Keywords: Animals; Exome; Female; Genetic Diseases, Inborn; Genetic Linkage; Genetic Variation; Genome-Wide Association Study; Genomics; High-Throughput Nucleotide Sequencing; Male; Mice; Mutation; Phenotype; Reproducibility of Results

Expanding the Molecular and Clinical Phenotype of SSR4-CDG. - Ng, Bobby G; Raymond, Kimiyo; Kircher, Martin; Buckingham, Kati J; Wood, Tim; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; Wong, Jonathan T S; Monteiro, Fabiola Paoli; Graham, Brett H; Jackson, Sheryl; et al. (Hum Mutat, 2015)
Congenital disorders of glycosylation (CDG) are a group of mostly autosomal recessive disorders primarily characterized by neurological abnormalities. Recently, we described a single CDG patient with a de novo mutation in the X-linked gene, Signal Sequence Receptor 4 (SSR4). We performed whole-exome sequencing to identify causal variants in several affected individuals who had either an undifferentiated neurological disorder or unsolved CDG of unknown etiology based on abnormal transferrin glycosylation. We now report eight affected males with either de novo (4) or inherited (4) loss of function mutations in SSR4. Western blot analysis revealed that the mutations caused a complete loss of SSR4 protein. In nearly all cases, the abnormal glycosylation of serum transferrin was only slightly above the accepted normal cutoff range.
Keywords: Calcium-Binding Proteins; Congenital Disorders of Glycosylation; DNA Mutational Analysis; Exome; Gene Order; Genes, X-Linked; Genetic Loci; Humans; Male; Membrane Glycoproteins; Mutation; Phenotype; Receptors, Cytoplasmic and Nuclear; Receptors, Peptide

FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Muzny, Donna; Gibbs, Richard A; Boerwinkle, Eric; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

Frequency and phenotypic spectrum of germline mutations in POLE and seven other polymerase genes in 266 patients with colorectal adenomas and carcinomas. - Spier, Isabel; Holzapfel, Stefanie; Altmüller, Janine; Zhao, Bixiao; Horpaopan, Sukanya; Vogt, Stefanie; Chen, Sophia; Morak, Monika; Raeder, Susanne; Kayser, Katrin; Stienen, Dietlinde; Adam, Ronja; et al. (Int J Cancer, 2015)
In a number of families with colorectal adenomatous polyposis or suspected Lynch syndrome/HNPCC, no germline alteration in the APC, MUTYH, or mismatch repair (MMR) genes are found. Missense mutations in the polymerase genes POLE and POLD1 have recently been identified as rare cause of multiple colorectal adenomas and carcinomas, a condition termed polymerase proofreading-associated polyposis (PPAP). The aim of the present study was to evaluate the clinical relevance and phenotypic spectrum of polymerase germline mutations. Therefore, targeted sequencing of the polymerase genes POLD1, POLD2, POLD3, POLD4, POLE, POLE2, POLE3 and POLE4 was performed in 266 unrelated patients with polyposis or fulfilled Amsterdam criteria. The POLE mutation c.1270C>G;p.Leu424Val was detected in four unrelated patients. The mutation was present in 1.5% (4/266) of all patients, 4% (3/77) of all familial cases and 7% (2/30) of familial polyposis cases. The colorectal phenotype in 14 affected individuals ranged from typical adenomatous polyposis to a HNPCC phenotype, with high intrafamilial variability. Multiple colorectal carcinomas and duodenal adenomas were common, and one case of duodenal carcinoma was reported. Additionally, various extraintestinal lesions were evident. Nine further putative pathogenic variants were identified. The most promising was c.1306C>T;p.Pro436Ser in POLE. In conclusion, a PPAP was identified in a substantial number of polyposis and familial colorectal cancer patients. Screening for polymerase proofreading mutations should therefore be considered, particularly in unexplained familial cases. The present study broadens the phenotypic spectrum of PPAP to duodenal adenomas and carcinomas, and identified novel, potentially pathogenic variants in four polymerase genes.
Keywords: Adenoma; Adolescent; Adult; Aged; Aged, 80 and over; Child; Colorectal Neoplasms; DNA Polymerase II; DNA-Directed DNA Polymerase; Family Health; Female; Gene Frequency; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Isoenzymes; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Phospholipase D; Poly-ADP-Ribose Binding Proteins; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Young Adult

Frequent somatic reversion of KRT1 mutations in ichthyosis with confetti. - Choate, Keith A; Lu, Yin; Zhou, Jing; Elias, Peter M; Zaidi, Samir; Paller, Amy S; Farhi, Anita; Nelson-Williams, Carol; Crumrine, Debra; Milstone, Leonard M; Lifton, Richard P (J Clin Invest, 2015)
Widespread reversion of genetic disease is rare; however, such events are particularly evident in some skin disorders in which normal clones develop on a background of affected skin. We previously demonstrated that mutations in keratin 10 (KRT10) cause ichthyosis with confetti (IWC), a severe dominant disorder that is characterized by progressive development of hundreds of normal skin spots via revertant mosaicism. Here, we report on a clinical and histological IWC subtype in which affected subjects have red, scaly skin at birth, experience worsening palmoplantar keratoderma in childhood, and develop hundreds of normal skin spots, beginning at around 20 years of age, that increase in size and number over time. We identified a causal de novo mutation in keratin 1 (KRT1). Similar to IWC-causing KRT10 mutations, this mutation in KRT1 resulted in a C-terminal frameshift, replacing 22 C-terminal amino acids with an alternate 30-residue peptide. Mutant KRT1 caused partial collapse of the cytoplasmic intermediate filament network and mislocalized to the nucleus. As with KRT10 mutations causing IWC, reversion of KRT1 mutations occurred via mitotic recombination. Because reversion is not observed with other disease-causing keratin mutations, the results of this study implicate KRT1 and KRT10 C-terminal frameshift mutations in the high frequency of revertant mosaicism in IWC.
Keywords: Adult; Age of Onset; Amino Acid Sequence; Cell Line, Tumor; Cell Nucleus; Child; Child, Preschool; Chromosomes, Human, Pair 12; Cytoskeleton; Frameshift Mutation; Humans; Ichthyosis; Intermediate Filaments; Keratin-1; Keratinocytes; Loss of Heterozygosity; Male; Molecular Sequence Data; Mosaicism; Phenotype; Polymorphism, Single Nucleotide; Protein Transport; Transfection

Functional genome-wide siRNA screen identifies KIAA0586 as mutated in Joubert syndrome. - Roosing, Susanne; Hofree, Matan; Kim, Sehyun; Scott, Eric; Copeland, Brett; Romani, Marta; Silhavy, Jennifer L; Rosti, Rasim O; Schroth, Jana; Mazza, Tommaso; Miccinilli, Elide; Zaki, Maha S; et al. (Elife, 2015)
Defective primary ciliogenesis or cilium stability forms the basis of human ciliopathies, including Joubert syndrome (JS), with defective cerebellar vermis development. We performed a high-content genome-wide small interfering RNA (siRNA) screen to identify genes regulating ciliogenesis as candidates for JS. We analyzed results with a supervised-learning approach, using SYSCILIA gold standard, Cildb3.0, a centriole siRNA screen and the GTex project, identifying 591 likely candidates. Intersection of this data with whole exome results from 145 individuals with unexplained JS identified six families with predominantly compound heterozygous mutations in KIAA0586. A c.428del base deletion in 0.1% of the general population was found in trans with a second mutation in an additional set of 9 of 163 unexplained JS patients. KIAA0586 is an orthologue of chick Talpid3, required for ciliogenesis and Sonic hedgehog signaling. Our results uncover a relatively high frequency cause for JS and contribute a list of candidates for future gene discoveries in ciliopathies.
Keywords: Abnormalities, Multiple; Cell Cycle Proteins; Cerebellum; Eye Abnormalities; Gene Frequency; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Heterozygote; Humans; Kidney Diseases, Cystic; Mutant Proteins; Retina; RNA, Small Interfering

GeneMatcher: a matching tool for connecting investigators with an interest in the same gene. - Sobreira, Nara; Schiettecatte, François; Valle, David; Hamosh, Ada (Hum Mutat, 2015)
Here, we describe an overview and update on GeneMatcher (http://www.genematcher.org), a freely accessible Web-based tool developed as part of the Baylor-Hopkins Center for Mendelian Genomics. We created GeneMatcher with the goal of identifying additional individuals with rare phenotypes who had variants in the same candidate disease gene. We also wanted to facilitate connections to basic scientists working on orthologous genes in model systems with the goal of connecting their work to human Mendelian phenotypes. Meeting these goals will enhance the identification of novel Mendelian genes. Launched in September, 2013, GeneMatcher now has 2,178 candidate genes from 486 submitters spread across 38 countries entered in the database (June 1, 2015). GeneMatcher is also part of the Matchmaker Exchange (http://matchmakerexchange.org/) with an Application Programing Interface enabling submitters to query other databases of genetic variants and phenotypes without having to create accounts and data entries in multiple systems.
Keywords: Computational Biology; Databases, Genetic; Genetic Predisposition to Disease; Genetic Variation; Humans; Information Dissemination; Phenotype; Rare Diseases; Software; User-Computer Interface; Web Browser

GeneMatcher aids in the identification of a new malformation syndrome with intellectual disability, unique facial dysmorphisms, and skeletal and connective tissue abnormalities caused by de novo variants in HNRNPK. - Au, P Y Billie; You, Jing; Caluseriu, Oana; Schwartzentruber, Jeremy; Majewski, Jacek; Bernier, Francois P; Ferguson, Marcia; Valle, David; Parboosingh, Jillian S; Sobreira, Nara; Innes, A Micheil; Kline, Antonie D (Hum Mutat, 2015)
We report a new syndrome due to loss-of-function variants in the heterogeneous nuclear ribonucleoprotein K gene (HNRNPK). We describe two probands: one with a de novo frameshift (NM_002140.3: c.953+1dup), and the other with a de novo splice donor site variant (NM_002140.3: c.257G>A). Both probands have intellectual disability, a shared unique craniofacial phenotype, and connective tissue and skeletal abnormalities. The identification of this syndrome was made possible by a new online tool, GeneMatcher, which facilitates connections between clinicians and researchers based on shared interest in candidate genes. This report demonstrates that new Web-based approaches can be effective in helping investigators solve exome sequencing projects, and also highlights the newer paradigm of "reverse phenotyping," where characterization of syndromic features follows the identification of genetic variants.
Keywords: Abnormalities, Multiple; Adolescent; Child; Craniofacial Abnormalities; Databases, Genetic; Genetic Predisposition to Disease; Heterogeneous-Nuclear Ribonucleoprotein K; Humans; Information Dissemination; Intellectual Disability; Male; Muscular Atrophy; Phenotype; Polymorphism, Single Nucleotide; Ribonucleoproteins; Software; Web Browser

Generation of sequence-based data for pedigree-segregating Mendelian or Complex traits. - Li, Biao; Wang, Gao T; Leal, Suzanne M (Bioinformatics, 2015)
MOTIVATION: There is great interest in analyzing next generation sequence data that has been generated for pedigrees. However, unlike for population-based data there are only a limited number of rare variant methods to analyze pedigree data. One limitation is the ability to evaluate type I and II errors for family-based methods, due to lack of software that can simulate realistic sequence data for pedigrees. SUMMARY: We developed RarePedSim (Rare-variant Pedigree-based Simulator), a program to simulate region/gene-level genotype and phenotype data for complex and Mendelian traits for any given pedigree structure. Using a genetic model, sequence variant data can be generated either conditionally or unconditionally on pedigree members' qualitative or quantitative phenotypes. Additionally, qualitative or quantitative traits can be generated conditional on variant data. Sequence data can either be simulated using realistic population demographic models or obtained from sequence-based studies. Variant sites can be annotated with positions, allele frequencies and functionality. For rare variants, RarePedSim is the only program that can efficiently generate both genotypes and phenotypes, regardless of pedigree structure. Data generated by RarePedSim are in standard Linkage file (.ped) and Variant Call (.vcf) formats, ready to be used for a variety of purposes, including evaluation of type I error and power, for association methods including mixed models and linkage analysis methods. AVAILABILITY AND IMPLEMENTATION: bioinformatics.org/simped/rare CONTACT: sleal@bcm.edu.
Keywords: Base Sequence; Chromosome Segregation; Humans; Pedigree; Quantitative Trait, Heritable; Sequence Analysis; Software

Genes that Affect Brain Structure and Function Identified by Rare Variant Analyses of Mendelian Neurologic Disease. - Karaca, Ender; Harel, Tamar; Pehlivan, Davut; Jhangiani, Shalini N; Gambin, Tomasz; Coban Akdemir, Zeynep; Gonzaga-Jauregui, Claudia; Erdin, Serkan; Bayram, Yavuz; Campbell, Ian M; Hunter, Jill V; Atik, Mehmed M; et al. (Neuron, 2015)
Development of the human nervous system involves complex interactions among fundamental cellular processes and requires a multitude of genes, many of which remain to be associated with human disease. We applied whole exome sequencing to 128 mostly consanguineous families with neurogenetic disorders that often included brain malformations. Rare variant analyses for both single nucleotide variant (SNV) and copy number variant (CNV) alleles allowed for identification of 45 novel variants in 43 known disease genes, 41 candidate genes, and CNVs in 10 families, with an overall potential molecular cause identified in >85% of families studied. Among the candidate genes identified, we found PRUNE, VARS, and DHX37 in multiple families and homozygous loss-of-function variants in AGBL2, SLC18A2, SMARCA1, UBQLN1, and CPLX1. Neuroimaging and in silico analysis of functional and expression proximity between candidate and known disease genes allowed for further understanding of genetic networks underlying specific types of brain malformations.
Keywords: Brain; Cohort Studies; Databases, Genetic; Female; Gene Regulatory Networks; Genetic Association Studies; Genetic Variation; Humans; Male; Mendelian Randomization Analysis; Nervous System Diseases; Pedigree

The Genetic Basis of Mendelian Phenotypes: Discoveries, Challenges, and Opportunities. - Chong, Jessica X; Buckingham, Kati J; Jhangiani, Shalini N; Boehm, Corinne; Sobreira, Nara; Smith, Joshua D; Harrell, Tanya M; McMillin, Margaret J; Wiszniewski, Wojciech; Gambin, Tomasz; Coban Akdemir, Zeynep H; Doheny, Kimberly; et al. (Am J Hum Genet, 2015)
Discovering the genetic basis of a Mendelian phenotype establishes a causal link between genotype and phenotype, making possible carrier and population screening and direct diagnosis. Such discoveries also contribute to our knowledge of gene function, gene regulation, development, and biological mechanisms that can be used for developing new therapeutics. As of February 2015, 2,937 genes underlying 4,163 Mendelian phenotypes have been discovered, but the genes underlying ∼50% (i.e., 3,152) of all known Mendelian phenotypes are still unknown, and many more Mendelian conditions have yet to be recognized. This is a formidable gap in biomedical knowledge. Accordingly, in December 2011, the NIH established the Centers for Mendelian Genomics (CMGs) to provide the collaborative framework and infrastructure necessary for undertaking large-scale whole-exome sequencing and discovery of the genetic variants responsible for Mendelian phenotypes. In partnership with 529 investigators from 261 institutions in 36 countries, the CMGs assessed 18,863 samples from 8,838 families representing 579 known and 470 novel Mendelian phenotypes as of January 2015. This collaborative effort has identified 956 genes, including 375 not previously associated with human health, that underlie a Mendelian phenotype. These results provide insight into study design and analytical strategies, identify novel mechanisms of disease, and reveal the extensive clinical variability of Mendelian phenotypes. Discovering the gene underlying every Mendelian phenotype will require tackling challenges such as worldwide ascertainment and phenotypic characterization of families affected by Mendelian conditions, improvement in sequencing and analytical techniques, and pervasive sharing of phenotypic and genomic data among researchers, clinicians, and families.
Keywords: Genetic Diseases, Inborn; Genetics, Medical; Humans; Phenotype; Proteins

Genetic linkage analysis in the age of whole-genome sequencing. - Ott, Jurg; Wang, Jing; Leal, Suzanne M (Nat Rev Genet, 2015)
For many years, linkage analysis was the primary tool used for the genetic mapping of Mendelian and complex traits with familial aggregation. Linkage analysis was largely supplanted by the wide adoption of genome-wide association studies (GWASs). However, with the recent increased use of whole-genome sequencing (WGS), linkage analysis is again emerging as an important and powerful analysis method for the identification of genes involved in disease aetiology, often in conjunction with WGS filtering approaches. Here, we review the principles of linkage analysis and provide practical guidelines for carrying out linkage studies using WGS data.
Keywords: Algorithms; Female; Genetic Linkage; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Lod Score; Male; Pedigree; Penetrance; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Software

Germline PRKACA amplification causes variable phenotypes that may depend on the extent of the genomic defect: molecular mechanisms and clinical presentations. - Lodish, Maya B; Yuan, Bo; Levy, Isaac; Braunstein, Glenn D; Lyssikatos, Charalampos; Salpea, Paraskevi; Szarek, Eva; Karageorgiadis, Alexander S; Belyavskaya, Elena; Raygada, Margarita; Faucz, Fabio Rueda; Izzat, Louise; et al. (Eur J Endocrinol, 2015)
OBJECTIVE: We have recently reported five patients with bilateral adrenocortical hyperplasia (BAH) and Cushing's syndrome (CS) caused by constitutive activation of the catalytic subunit of protein kinase A (PRKACA). By doing new in-depth analysis of their cytogenetic abnormality, we attempted a better genotype-phenotype correlation of their PRKACA amplification. DESIGN: This study is a case series. METHODS: Molecular cytogenetic, genomic, clinical, and histopathological analyses were performed in five patients with CS. RESULTS: Reinvestigation of the defects of previously described patients by state-of-the-art molecular cytogenetics showed complex genomic rearrangements in the chromosome 19p13.2p13.12 locus, resulting in copy number gains encompassing the entire PRKACA gene; three patients (one sporadic case and two related cases) were observed with gains consistent with duplications, while two sporadic patients were observed with gains consistent with triplications. Although all five patients presented with ACTH-independent CS, the three sporadic patients had micronodular BAH and underwent bilateral adrenalectomy in early childhood, whereas the two related patients, a mother and a son, presented with macronodular BAH as adults. In at least one patient, PRKACA triplication was associated with a more severe phenotype. CONCLUSIONS: Constitutional chromosomal PRKACA gene amplification is a recently identified genetic defect associated with CS, a trait that may be inherited in an autosomal dominant manner or occur de novo. Genomic rearrangements can be complex and can result in different copy number states of dosage-sensitive genes, e.g., duplication and triplication. PRKACA amplification can lead to variable phenotypes clinically and pathologically, both micro- and macro-nodular BAH, the latter of which we speculate may depend on the extent of amplification.
Keywords: Adrenal Glands; Adrenalectomy; Adult; Child; Child, Preschool; Cushing Syndrome; Cyclic AMP-Dependent Protein Kinase Catalytic Subunits; DNA Copy Number Variations; Female; Gene Amplification; Humans; Hyperplasia; Male; Phenotype; Young Adult

Global transcriptional disturbances underlie Cornelia de Lange syndrome and related phenotypes. - Yuan, Bo; Pehlivan, Davut; Karaca, Ender; Patel, Nisha; Charng, Wu-Lin; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Sutton, V Reid; Yesil, Gözde; Bozdogan, Sevcan Tug; Tos, Tulay; Koparir, Asuman; et al. (J Clin Invest, 2015)
Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder that presents with extensive phenotypic variability, including facial dysmorphism, developmental delay/intellectual disability (DD/ID), abnormal extremities, and hirsutism. About 65% of patients harbor mutations in genes that encode subunits or regulators of the cohesin complex, including NIPBL, SMC1A, SMC3, RAD21, and HDAC8. Wiedemann-Steiner syndrome (WDSTS), which shares CdLS phenotypic features, is caused by mutations in lysine-specific methyltransferase 2A (KMT2A). Here, we performed whole-exome sequencing (WES) of 2 male siblings clinically diagnosed with WDSTS; this revealed a hemizygous, missense mutation in SMC1A that was predicted to be deleterious. Extensive clinical evaluation and WES of 32 Turkish patients clinically diagnosed with CdLS revealed the presence of a de novo heterozygous nonsense KMT2A mutation in 1 patient without characteristic WDSTS features. We also identified de novo heterozygous mutations in SMC3 or SMC1A that affected RNA splicing in 2 independent patients with combined CdLS and WDSTS features. Furthermore, in families from 2 separate world populations segregating an autosomal-recessive disorder with CdLS-like features, we identified homozygous mutations in TAF6, which encodes a core transcriptional regulatory pathway component. Together, our data, along with recent transcriptome studies, suggest that CdLS and related phenotypes may be "transcriptomopathies" rather than cohesinopathies.
Keywords: Adolescent; Adult; Cell Cycle Proteins; Child; Child, Preschool; Chondroitin Sulfate Proteoglycans; Chromosomal Proteins, Non-Histone; Codon, Nonsense; De Lange Syndrome; Exome; Exonucleases; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Heterozygote; Histone Deacetylases; Histone-Lysine N-Methyltransferase; Humans; Infant; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Proteins; Repressor Proteins; Transcriptome

Homozygous loss-of-function mutations in SOHLH1 in patients with nonsyndromic hypergonadotropic hypogonadism. - Bayram, Yavuz; Gulsuner, Suleyman; Guran, Tulay; Abaci, Ayhan; Yesil, Gözde; Gulsuner, Hilal Unal; Atay, Zeynep; Pierce, Sarah B; Gambin, Tomasz; Lee, Ming; Turan, Serap; Bober, Ece; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Hypergonadotropic hypogonadism presents in females with delayed or arrested puberty, primary or secondary amenorrhea due to gonadal dysfunction, and is further characterized by elevated gonadotropins and low sex steroids. Chromosomal aberrations and various specific gene defects can lead to hypergonadotropic hypogonadism. Responsible genes include those with roles in gonadal development or maintenance, sex steroid synthesis, or end-organ resistance to gonadotropins. Identification of novel causative genes in this disorder will contribute to our understanding of the regulation of human reproductive function. OBJECTIVES: The aim of this study was to identify and report the gene responsible for autosomal-recessive hypergonadotropic hypogonadism in two unrelated families. DESIGN AND PARTICIPANTS: Clinical evaluation and whole-exome sequencing were performed in two pairs of sisters with nonsyndromic hypergonadotropic hypogonadism from two unrelated families. RESULTS: Exome sequencing analysis revealed two different truncating mutations in the same gene: SOHLH1 c.705delT (p.Pro235fs*4) and SOHLH1 c.27C>G (p.Tyr9stop). Both mutations were unique to the families and segregation was consistent with Mendelian expectations for an autosomal-recessive mode of inheritance. CONCLUSIONS: Sohlh1 was known from previous mouse studies to be a transcriptional regulator that functions in the maintenance and survival of primordial ovarian follicles, but loss-of-function mutations in human females have not been reported. Our results provide evidence that homozygous-truncating mutations in SOHLH1 cause female nonsyndromic hypergonadotropic hypogonadism.
Keywords: Adolescent; Basic Helix-Loop-Helix Transcription Factors; Child; Exome; Female; Homozygote; Humans; Hypogonadism; Mutation

A homozygous missense variant in type I keratin KRT25 causes autosomal recessive woolly hair. - Ansar, Muhammad; Raza, Syed Irfan; Lee, Kwanghyuk; Shahi, Shamim; Acharya, Anushree; Dai, Hang; Smith, Joshua D; Shendure, Jay; Bamshad, Michael J; Nickerson, Deborah A; Santos-Cortez, Regie Lyn P; Ahmad, Wasim; et al. (J Med Genet, 2015)
BACKGROUND: Woolly hair (WH) is a hair abnormality that is primarily characterised by tightly curled hair with abnormal growth. METHODS: In two unrelated consanguineous Pakistani families with non-syndromic autosomal recessive (AR) WH, homozygosity mapping and linkage analysis identified a locus within 17q21.1-q22, which contains the type I keratin gene cluster. A DNA sample from an affected individual from each family underwent exome sequencing. RESULTS: A homozygous missense variant c.950T>C (p.(Leu317Pro)) within KRT25 segregated with ARWH in both families, and has a combined maximum two-point LOD score of 7.9 at ϴ=0. The KRT25 variant is predicted to result in disruption of the second α-helical rod domain and the entire protein structure, thus possibly interfering with heterodimerisation of K25 with type II keratins within the inner root sheath (IRS) of the hair follicle and the medulla of the hair shaft. CONCLUSIONS: Our findings implicate a novel gene involved in human hair abnormality, and are consistent with the curled, fragile hair found in mice with Krt25 mutations, and further support the role of IRS-specific type I keratins in hair follicle development and maintenance of hair texture.
Keywords: Child; Child, Preschool; Consanguinity; Hair; Hair Diseases; Humans; Keratins, Type I; Male; Mutation, Missense; Pakistan; Pedigree; Sequence Analysis, DNA

Identification and functional characterization of natural human melanocortin 1 receptor mutant alleles in Pakistani population. - Shahzad, Mohsin; Sires Campos, Julia; Tariq, Nabeela; Herraiz Serrano, Cecilia; Yousaf, Rizwan; Jiménez-Cervantes, Celia; Yousaf, Sairah; Waryah, Yar M; Dad, Haseeb A; Blue, Elizabeth M; Sobreira, Nara; López-Giráldez, Francesc; et al. (Pigment Cell Melanoma Res, 2015)
Melanocortin 1 receptor (MC1R), a Gs protein-coupled receptor of the melanocyte's plasma membrane, is a major determinant of skin pigmentation and phototype. Upon activation by α-melanocyte stimulating hormone, MC1R triggers the cAMP cascade to stimulate eumelanogenesis. We used whole-exome sequencing to identify causative alleles in Pakistani families with skin and hair hypopigmentation. Six MC1R mutations segregated with the phenotype in seven families, including a p.Val174del in-frame deletion and a p.Tyr298* nonsense mutation, that were analyzed for function in heterologous HEK293 cells. p.Tyr298* MC1R showed no agonist-induced signaling to the cAMP or ERK pathways, nor detectable agonist binding. Conversely, signaling was comparable for p.Val174del and wild-type in HEK cells overexpressing the proteins, but binding analysis suggested impaired cell surface expression. Flow cytometry and confocal imaging studies revealed reduced plasma membrane expression of p.Val174del and p.Tyr298*. Therefore, p.Tyr298* was a total loss-of-function (LOF) allele, while p.Val174del displayed a partial LOF attribute.
Keywords: Alleles; Family; Female; Humans; Hypopigmentation; Male; Mutation; Pakistan; Pedigree; Phenotype; Receptor, Melanocortin, Type 1

Inactivating mutations in MFSD2A, required for omega-3 fatty acid transport in brain, cause a lethal microcephaly syndrome. - Guemez-Gamboa, Alicia; Nguyen, Long N; Yang, Hongbo; Zaki, Maha S; Kara, Majdi; Ben-Omran, Tawfeg; Akizu, Naiara; Rosti, Rasim Ozgur; Rosti, Basak; Scott, Eric; Schroth, Jana; Copeland, Brett; et al. (Nat Genet, 2015)
Docosahexanoic acid (DHA) is the most abundant omega-3 fatty acid in brain, and, although it is considered essential, deficiency has not been linked to disease. Despite the large mass of DHA in phospholipids, the brain does not synthesize it. DHA is imported across the blood-brain barrier (BBB) through the major facilitator superfamily domain-containing 2a (MFSD2A) protein. MFSD2A transports DHA as well as other fatty acids in the form of lysophosphatidylcholine (LPC). We identify two families displaying MFSD2A mutations in conserved residues. Affected individuals exhibited a lethal microcephaly syndrome linked to inadequate uptake of LPC lipids. The MFSD2A mutations impaired transport activity in a cell-based assay. Moreover, when expressed in mfsd2aa-morphant zebrafish, mutants failed to rescue microcephaly, BBB breakdown and lethality. Our results establish a link between transport of DHA and LPCs by MFSD2A and human brain growth and function, presenting the first evidence of monogenic disease related to transport of DHA in humans.
Keywords: Adolescent; Animals; Biological Transport; Blood-Brain Barrier; Brain; Case-Control Studies; Child; Child, Preschool; Consanguinity; Fatty Acids, Omega-3; Female; Genes, Lethal; Genetic Association Studies; HEK293 Cells; Humans; Infant; Male; Mice, Knockout; Microcephaly; Mutation, Missense; Syndrome; Tumor Suppressor Proteins; Zebrafish

Joubert syndrome: a model for untangling recessive disorders with extreme genetic heterogeneity. - Bachmann-Gagescu, R; Dempsey, J C; Phelps, I G; O'Roak, B J; Knutzen, D M; Rue, T C; Ishak, G E; Isabella, C R; Gorden, N; Adkins, J; Boyle, E A; de Lacy, N; et al. (J Med Genet, 2015)
BACKGROUND: Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterised by hypotonia, ataxia, cognitive impairment, abnormal eye movements, respiratory control disturbances and a distinctive mid-hindbrain malformation. JS demonstrates substantial phenotypic variability and genetic heterogeneity. This study provides a comprehensive view of the current genetic basis, phenotypic range and gene-phenotype associations in JS. METHODS: We sequenced 27 JS-associated genes in 440 affected individuals (375 families) from a cohort of 532 individuals (440 families) with JS, using molecular inversion probe-based targeted capture and next-generation sequencing. Variant pathogenicity was defined using the Combined Annotation Dependent Depletion algorithm with an optimised score cut-off. RESULTS: We identified presumed causal variants in 62% of pedigrees, including the first B9D2 mutations associated with JS. 253 different mutations in 23 genes highlight the extreme genetic heterogeneity of JS. Phenotypic analysis revealed that only 34% of individuals have a 'pure JS' phenotype. Retinal disease is present in 30% of individuals, renal disease in 25%, coloboma in 17%, polydactyly in 15%, liver fibrosis in 14% and encephalocele in 8%. Loss of CEP290 function is associated with retinal dystrophy, while loss of TMEM67 function is associated with liver fibrosis and coloboma, but we observe no clear-cut distinction between JS subtypes. CONCLUSIONS: This work illustrates how combining advanced sequencing techniques with phenotypic data addresses extreme genetic heterogeneity to provide diagnostic and carrier testing, guide medical monitoring for progressive complications, facilitate interpretation of genome-wide sequencing results in individuals with a variety of phenotypes and enable gene-specific treatments in the future.
Keywords: Abnormalities, Multiple; Cerebellum; Cohort Studies; DNA Mutational Analysis; Eye Abnormalities; Genetic Association Studies; Genetic Heterogeneity; Humans; Kidney Diseases, Cystic; Models, Theoretical; Pedigree; Retina; Sequence Analysis, DNA

KIAA0586 is Mutated in Joubert Syndrome. - Bachmann-Gagescu, Ruxandra; Phelps, Ian G; Dempsey, Jennifer C; Sharma, Vivek A; Ishak, Gisele E; Boyle, Evan A; Wilson, Meredith; Marques Lourenço, Charles; Arslan, Mutluay; Shendure, Jay; Doherty, Dan (Hum Mutat, 2015)
Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterized by a distinctive mid-hindbrain malformation. JS is part of a group of disorders called ciliopathies based on their overlapping phenotypes and common underlying pathophysiology linked to primary cilium dysfunction. Biallelic mutations in one of 28 genes, all encoding proteins localizing to the primary cilium or basal body, can cause JS. Despite this large number of genes, the genetic cause can currently be determined in about 62% of individuals with JS. To identify novel JS genes, we performed whole exome sequencing on 35 individuals with JS and found biallelic rare deleterious variants (RDVs) in KIAA0586, encoding a centrosomal protein required for ciliogenesis, in one individual. Targeted next-generation sequencing in a large JS cohort identified biallelic RDVs in eight additional families for an estimated prevalence of 2.5% (9/366 JS families). All affected individuals displayed JS phenotypes toward the mild end of the spectrum.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Alternative Splicing; Brain; Cell Cycle Proteins; Cerebellum; Child; Child, Preschool; DNA Mutational Analysis; Eye Abnormalities; Gene Order; Genetic Association Studies; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Mutation; Phenotype; Retina; Young Adult

The Matchmaker Exchange: a platform for rare disease gene discovery. - Philippakis, Anthony A; Azzariti, Danielle R; Beltran, Sergi; Brookes, Anthony J; Brownstein, Catherine A; Brudno, Michael; Brunner, Han G; Buske, Orion J; Carey, Knox; Doll, Cassie; Dumitriu, Sergiu; Dyke, Stephanie O M; et al. (Hum Mutat, 2015)
There are few better examples of the need for data sharing than in the rare disease community, where patients, physicians, and researchers must search for "the needle in a haystack" to uncover rare, novel causes of disease within the genome. Impeding the pace of discovery has been the existence of many small siloed datasets within individual research or clinical laboratory databases and/or disease-specific organizations, hoping for serendipitous occasions when two distant investigators happen to learn they have a rare phenotype in common and can "match" these cases to build evidence for causality. However, serendipity has never proven to be a reliable or scalable approach in science. As such, the Matchmaker Exchange (MME) was launched to provide a robust and systematic approach to rare disease gene discovery through the creation of a federated network connecting databases of genotypes and rare phenotypes using a common application programming interface (API). The core building blocks of the MME have been defined and assembled. Three MME services have now been connected through the API and are available for community use. Additional databases that support internal matching are anticipated to join the MME network as it continues to grow.
Keywords: Database Management Systems; Databases, Genetic; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Information Dissemination; Rare Diseases; Software

The Matchmaker Exchange API: automating patient matching through the exchange of structured phenotypic and genotypic profiles. - Buske, Orion J; Schiettecatte, François; Hutton, Benjamin; Dumitriu, Sergiu; Misyura, Andriy; Huang, Lijia; Hartley, Taila; Girdea, Marta; Sobreira, Nara; Mungall, Chris; Brudno, Michael (Hum Mutat, 2015)
Despite the increasing prevalence of clinical sequencing, the difficulty of identifying additional affected families is a key obstacle to solving many rare diseases. There may only be a handful of similar patients worldwide, and their data may be stored in diverse clinical and research databases. Computational methods are necessary to enable finding similar patients across the growing number of patient repositories and registries. We present the Matchmaker Exchange Application Programming Interface (MME API), a protocol and data format for exchanging phenotype and genotype profiles to enable matchmaking among patient databases, facilitate the identification of additional cohorts, and increase the rate with which rare diseases can be researched and diagnosed. We designed the API to be straightforward and flexible in order to simplify its adoption on a large number of data types and workflows. We also provide a public test data set, curated from the literature, to facilitate implementation of the API and development of new matching algorithms. The initial version of the API has been successfully implemented by three members of the Matchmaker Exchange and was immediately able to reproduce previously identified matches and generate several new leads currently being validated. The API is available at https://github.com/ga4gh/mme-apis.
Keywords: Algorithms; Computational Biology; Databases, Genetic; Genetic Predisposition to Disease; Genotype; Humans; Information Dissemination; Phenotype; Rare Diseases; Web Browser

Mutation in GM2A Leads to a Progressive Chorea-dementia Syndrome. - Salih, Mustafa A; Seidahmed, Mohammed Z; El Khashab, Heba Y; Hamad, Muddathir H A; Bosley, Thomas M; Burn, Sabrina; Myers, Angela; Landsverk, Megan L; Crotwell, Patricia L; Bilguvar, Kaya; Mane, Shrikant; Kruer, Michael C (Tremor Other Hyperkinet Mov (N Y), 2015)
BACKGROUND: The etiology of many cases of childhood-onset chorea remains undetermined, although advances in genomics are revealing both new disease-associated genes and variant phenotypes associated with known genes. METHODS: We report a Saudi family with a neurodegenerative course dominated by progressive chorea and dementia in whom we performed homozygosity mapping and whole exome sequencing. RESULTS: We identified a homozygous missense mutation in GM2A within a prominent block of homozygosity. This mutation is predicted to impair protein function. DISCUSSION: Although discovered more than two decades ago, to date, only five patients with this rare form of GM2 gangliosidosis have been reported. The phenotype of previously described GM2A patients has been typified by onset in infancy, profound hypotonia and impaired volitional movement, intractable seizures, hyperacusis, and a macular cherry red spot. Our findings expand the phenotypic spectrum of GM2A mutation-positive gangliosidosis to include generalized chorea without macular findings or hyperacusis and highlight how mutations in neurodegenerative disease genes may present in unexpected ways.

Mutation of ATF6 causes autosomal recessive achromatopsia. - Ansar, Muhammad; Santos-Cortez, Regie Lyn P; Saqib, Muhammad Arif Nadeem; Zulfiqar, Fareeha; Lee, Kwanghyuk; Ashraf, Naeem Mahmood; Ullah, Ehsan; Wang, Xin; Sajid, Sundus; Khan, Falak Sher; Amin-ud-Din, Muhammad; Smith, Joshua D; et al. (Hum Genet, 2015)
Achromatopsia (ACHM) is an early-onset retinal dystrophy characterized by photophobia, nystagmus, color blindness and severely reduced visual acuity. Currently mutations in five genes CNGA3, CNGB3, GNAT2, PDE6C and PDE6H have been implicated in ACHM. We performed homozygosity mapping and linkage analysis in a consanguineous Pakistani ACHM family and mapped the locus to a 15.12-Mb region on chromosome 1q23.1-q24.3 with a maximum LOD score of 3.6. A DNA sample from an affected family member underwent exome sequencing. Within the ATF6 gene, a single-base insertion variant c.355_356dupG (p.Glu119Glyfs*8) was identified, which completely segregates with the ACHM phenotype within the family. The frameshift variant was absent in public variant databases, in 130 exomes from unrelated Pakistani individuals, and in 235 ethnically matched controls. The variant is predicted to result in a truncated protein that lacks the DNA binding and transmembrane domains and therefore affects the function of ATF6 as a transcription factor that initiates the unfolded protein response during endoplasmic reticulum (ER) stress. Immunolabeling with anti-ATF6 antibodies showed localization throughout the mouse neuronal retina, including retinal pigment epithelium, photoreceptor cells, inner nuclear layer, inner and outer plexiform layers, with a more prominent signal in retinal ganglion cells. In contrast to cytoplasmic expression of wild-type protein, in heterologous cells ATF6 protein with the p.Glu119Glyfs*8 variant is mainly confined to the nucleus. Our results imply that response to ER stress as mediated by the ATF6 pathway is essential for color vision in humans.
Keywords: Activating Transcription Factor 6; Adolescent; Animals; Asian Continental Ancestry Group; Color Vision Defects; Consanguinity; DNA Mutational Analysis; Exome; Female; Frameshift Mutation; Genotyping Techniques; Homozygote; Humans; Limit of Detection; Male; Mice; Mice, Inbred C57BL; Pakistan; Pedigree; Phenotype; Retina; Signal Transduction

Mutations in COL27A1 cause Steel syndrome and suggest a founder mutation effect in the Puerto Rican population. - Gonzaga-Jauregui, Claudia; Gamble, Candace N; Yuan, Bo; Penney, Samantha; Jhangiani, Shalini; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; Hecht, Jacqueline T (Eur J Hum Genet, 2015)
Osteochondrodysplasias represent a large group of developmental structural disorders that can be caused by mutations in a variety of genes responsible for chondrocyte development, differentiation, mineralization and early ossification. The application of whole-exome sequencing to disorders apparently segregating as Mendelian traits has proven to be an effective approach to disease gene identification for conditions with unknown molecular etiology. We identified a homozygous missense variant p.(Gly697Arg) in COL27A1, in a family with Steel syndrome and no consanguinity. Interestingly, the identified variant seems to have arisen as a founder mutation in the Puerto Rican population.
Keywords: Amino Acid Sequence; Child, Preschool; Comparative Genomic Hybridization; Exome; Female; Fibrillar Collagens; Follow-Up Studies; Founder Effect; Genotype; Hispanic Americans; Humans; Infant; Male; Molecular Sequence Data; Mutation; Osteochondrodysplasias; Pedigree; Polymorphism, Single Nucleotide; Prostaglandins F; Puerto Rico; Sequence Alignment

Mutations in DYNC2LI1 disrupt cilia function and cause short rib polydactyly syndrome. - Taylor, S Paige; Dantas, Tiago J; Duran, Ivan; Wu, Sulin; Lachman, Ralph S; Nelson, Stanley F; Cohn, Daniel H; Vallee, Richard B; Krakow, Deborah (Nat Commun, 2015)
The short rib polydactyly syndromes (SRPSs) are a heterogeneous group of autosomal recessive, perinatal lethal skeletal disorders characterized primarily by short, horizontal ribs, short limbs and polydactyly. Mutations in several genes affecting intraflagellar transport (IFT) cause SRPS but they do not account for all cases. Here we identify an additional SRPS gene and further unravel the functional basis for IFT. We perform whole-exome sequencing and identify mutations in a new disease-producing gene, cytoplasmic dynein-2 light intermediate chain 1, DYNC2LI1, segregating with disease in three families. Using primary fibroblasts, we show that DYNC2LI1 is essential for dynein-2 complex stability and that mutations in DYNC2LI1 result in variable length, including hyperelongated, cilia, Hedgehog pathway impairment and ciliary IFT accumulations. The findings in this study expand our understanding of SRPS locus heterogeneity and demonstrate the importance of DYNC2LI1 in dynein-2 complex stability, cilium function, Hedgehog regulation and skeletogenesis.
Keywords: Biological Transport; Cilia; Cytoplasmic Dyneins; Cytoskeleton; Female; Fibroblasts; Flagella; Hedgehog Proteins; Humans; Male; Mutation; Pedigree; Short Rib-Polydactyly Syndrome

Mutations in Either TUBB or MAPRE2 Cause Circumferential Skin Creases Kunze Type. - Isrie, Mala; Breuss, Martin; Tian, Guoling; Hansen, Andi Harley; Cristofoli, Francesca; Morandell, Jasmin; Kupchinsky, Zachari A; Sifrim, Alejandro; Rodriguez-Rodriguez, Celia Maria; Dapena, Elena Porta; Doonanco, Kurston; Leonard, Norma; et al. (Am J Hum Genet, 2015)
Circumferential skin creases Kunze type (CSC-KT) is a specific congenital entity with an unknown genetic cause. The disease phenotype comprises characteristic circumferential skin creases accompanied by intellectual disability, a cleft palate, short stature, and dysmorphic features. Here, we report that mutations in either MAPRE2 or TUBB underlie the genetic origin of this syndrome. MAPRE2 encodes a member of the microtubule end-binding family of proteins that bind to the guanosine triphosphate cap at growing microtubule plus ends, and TUBB encodes a β-tubulin isotype that is expressed abundantly in the developing brain. Functional analyses of the TUBB mutants show multiple defects in the chaperone-dependent tubulin heterodimer folding and assembly pathway that leads to a compromised yield of native heterodimers. The TUBB mutations also have an impact on microtubule dynamics. For MAPRE2, we show that the mutations result in enhanced MAPRE2 binding to microtubules, implying an increased dwell time at microtubule plus ends. Further, in vivo analysis of MAPRE2 mutations in a zebrafish model of craniofacial development shows that the variants most likely perturb the patterning of branchial arches, either through excessive activity (under a recessive paradigm) or through haploinsufficiency (dominant de novo paradigm). Taken together, our data add CSC-KT to the growing list of tubulinopathies and highlight how multiple inheritance paradigms can affect dosage-sensitive biological systems so as to result in the same clinical defect.
Keywords: Adolescent; Animals; Brain; Child; Cutis Laxa; Female; Gene Dosage; Gene Expression Regulation, Developmental; Genes, Recessive; Hamartoma; Haploinsufficiency; Humans; Infant; Inheritance Patterns; Male; Microtubule-Associated Proteins; Microtubules; Mutation; Protein Folding; Protein Multimerization; Skin; Skin Abnormalities; Tubulin; Young Adult; Zebrafish

Mutations in RAD21 disrupt regulation of APOB in patients with chronic intestinal pseudo-obstruction. - Bonora, Elena; Bianco, Francesca; Cordeddu, Lina; Bamshad, Michael; Francescatto, Ludmila; Dowless, Dustin; Stanghellini, Vincenzo; Cogliandro, Rosanna F; Lindberg, Greger; Mungan, Zeynel; Cefle, Kivanc; Ozcelik, Tayfun; et al. (Gastroenterology, 2015)
BACKGROUND & AIMS: Chronic intestinal pseudo-obstruction (CIPO) is characterized by severe intestinal dysmotility that mimics a mechanical subocclusion with no evidence of gut obstruction. We searched for genetic variants associated with CIPO to increase our understanding of its pathogenesis and to identify potential biomarkers. METHODS: We performed whole-exome sequencing of genomic DNA from patients with familial CIPO syndrome. Blood and lymphoblastoid cells were collected from patients and controls (individuals without CIPO); levels of messenger RNA (mRNA) and proteins were analyzed by quantitative reverse-transcription polymerase chain reaction, immunoblot, and mobility shift assays. Complementary DNAs were transfected into HEK293 cells. Expression of rad21 was suppressed in zebrafish embryos using a splice-blocking morpholino (rad21a). Gut tissues were collected and analyzed. RESULTS: We identified a homozygous mutation (p.622, encodes Ala>Thr) in RAD21 in patients from a consanguineous family with CIPO. Expression of RUNX1, a target of RAD21, was reduced in cells from patients with CIPO compared with controls. In zebrafish, suppression of rad21a reduced expression of runx1; this phenotype was corrected by injection of human RAD21 mRNA, but not with the mRNA from the mutated p.622 allele. rad21a Morpholino zebrafish had delayed intestinal transit and greatly reduced numbers of enteric neurons, similar to patients with CIPO. This defect was greater in zebrafish with suppressed expression of ret and rad21, indicating their interaction in the regulation of gut neurogenesis. The promoter region of APOB bound RAD21 but not RAD21 p.622 Ala>Thr; expression of wild-type RAD21 in HEK293 cells repressed expression of APOB, compared with control vector. The gut-specific isoform of APOB (APOB48) is overexpressed in sera from patients with CIPO who carry the RAD21 mutation. APOB48 also is overexpressed in sporadic CIPO in sera and gut biopsy specimens. CONCLUSIONS: Some patients with CIPO carry mutations in RAD21 that disrupt the ability of its product to regulate genes such as RUNX1 and APOB. Reduced expression of rad21 in zebrafish, and dysregulation of these target genes, disrupts intestinal transit and the development of enteric neurons.
Keywords: Adult; Animals; Apolipoprotein B-100; Case-Control Studies; Cell Cycle Proteins; Chronic Disease; Core Binding Factor Alpha 2 Subunit; Enteric Nervous System; Female; Gastrointestinal Motility; Gene Expression Profiling; Gene Knockdown Techniques; HEK293 Cells; Humans; Intestinal Pseudo-Obstruction; Male; Middle Aged; Nuclear Proteins; Phosphoproteins; RNA, Messenger; Sequence Analysis, DNA; Young Adult; Zebrafish; Zebrafish Proteins

Mutations in SPATA5 Are Associated with Microcephaly, Intellectual Disability, Seizures, and Hearing Loss. - Tanaka, Akemi J; Cho, Megan T; Millan, Francisca; Juusola, Jane; Retterer, Kyle; Joshi, Charuta; Niyazov, Dmitriy; Garnica, Adolfo; Gratz, Edward; Deardorff, Matthew; Wilkins, Alisha; Ortiz-Gonzalez, Xilma; et al. (Am J Hum Genet, 2015)
Using whole-exome sequencing, we have identified in ten families 14 individuals with microcephaly, developmental delay, intellectual disability, hypotonia, spasticity, seizures, sensorineural hearing loss, cortical visual impairment, and rare autosomal-recessive predicted pathogenic variants in spermatogenesis-associated protein 5 (SPATA5). SPATA5 encodes a ubiquitously expressed member of the ATPase associated with diverse activities (AAA) protein family and is involved in mitochondrial morphogenesis during early spermatogenesis. It might also play a role in post-translational modification during cell differentiation in neuronal development. Mutations in SPATA5 might affect brain development and function, resulting in microcephaly, developmental delay, and intellectual disability.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Base Sequence; Exome; Female; Gene Frequency; Genes, Recessive; Hearing Loss; Homeodomain Proteins; Humans; Intellectual Disability; Male; Microcephaly; Molecular Sequence Data; Mutation; Seizures; Sequence Alignment; Sequence Analysis, DNA

Mutations in TBX18 Cause Dominant Urinary Tract Malformations via Transcriptional Dysregulation of Ureter Development. - Vivante, Asaf; Kleppa, Marc-Jens; Schulz, Julian; Kohl, Stefan; Sharma, Amita; Chen, Jing; Shril, Shirlee; Hwang, Daw-Yang; Weiss, Anna-Carina; Kaminski, Michael M; Shukrun, Rachel; Kemper, Markus J; et al. (Am J Hum Genet, 2015)
Congenital anomalies of the kidneys and urinary tract (CAKUT) are the most common cause of chronic kidney disease in the first three decades of life. Identification of single-gene mutations that cause CAKUT permits the first insights into related disease mechanisms. However, for most cases the underlying defect remains elusive. We identified a kindred with an autosomal-dominant form of CAKUT with predominant ureteropelvic junction obstruction. By whole exome sequencing, we identified a heterozygous truncating mutation (c.1010delG) of T-Box transcription factor 18 (TBX18) in seven affected members of the large kindred. A screen of additional families with CAKUT identified three families harboring two heterozygous TBX18 mutations (c.1570C>T and c.487A>G). TBX18 is essential for developmental specification of the ureteric mesenchyme and ureteric smooth muscle cells. We found that all three TBX18 altered proteins still dimerized with the wild-type protein but had prolonged protein half life and exhibited reduced transcriptional repression activity compared to wild-type TBX18. The p.Lys163Glu substitution altered an amino acid residue critical for TBX18-DNA interaction, resulting in impaired TBX18-DNA binding. These data indicate that dominant-negative TBX18 mutations cause human CAKUT by interference with TBX18 transcriptional repression, thus implicating ureter smooth muscle cell development in the pathogenesis of human CAKUT.
Keywords: Base Sequence; Electrophoretic Mobility Shift Assay; Exome; Gene Expression Regulation, Developmental; Genes, Dominant; HEK293 Cells; Humans; Immunohistochemistry; Immunoprecipitation; Microscopy, Fluorescence; Molecular Sequence Data; Muscle, Smooth; Mutation; Pedigree; Sequence Analysis, DNA; T-Box Domain Proteins; Ureter; Urinary Tract

New Arab family with cerebral dysgenesis, neuropathy, ichthyosis and keratoderma syndrome suggests a possible founder effect for the c.223delG mutation. - Ben-Salem, Salma; Nara, Sobreira; Al-Shamsi, Aisha M; Valle, David; Ali, Bassam R; Al-Gazali, Lihadh (J Dermatol, 2015)
Keywords: Arabs; Female; Founder Effect; Humans; Infant, Newborn; Keratoderma, Palmoplantar; Neurocutaneous Syndromes; Qb-SNARE Proteins; Qc-SNARE Proteins

New mutations in the RAB28 gene in 2 Spanish families with cone-rod dystrophy. - Riveiro-Álvarez, Rosa; Xie, Yajing Angela; López-Martínez, Miguel-Ángel; Gambin, Tomasz; Pérez-Carro, Raquel; Ávila-Fernández, Almudena; López-Molina, María-Isabel; Zernant, Jana; Jhangiani, Shalini; Muzny, Donna; Yuan, Bo; Boerwinkle, Eric; et al. (JAMA Ophthalmol, 2015)
IMPORTANCE: The families evaluated in this study represent the second report of cone-rod dystrophy (CRD) cases caused by mutations in RAB28, a recently discovered gene associated with CRD. OBJECTIVE: To determine the disease-causing gene in 2 families of Spanish descent presenting with CRD who do not have ABCA4 mutations. DESIGN, SETTING, AND PARTICIPANTS: Molecular genetics and observational case studies of 2 families, each with 1 affected proband with CRD and 3 or 5 unaffected family members. The affected individual from each family received a complete ophthalmic examination including assessment of refractive errors and best-corrected visual acuity, biomicroscopy, color fundus photography, electroretinography analysis, and visual-evoked potential analysis. After complete sequencing of the ABCA4 gene with negative results, the screening for disease-causing mutations was performed by whole-exome sequencing. Possible disease-associated variants were determined by filtering based on minor allele frequency, predicted pathogenicity, and segregation analysis in all family members. MAIN OUTCOMES AND MEASURES: The appearance of the macula was evaluated by clinical examination, fundus photography, and fundus autofluorescence imaging, and visual function was assessed by electroretinography. Disease-causing mutations were assessed by sequence analyses. RESULTS: Ophthalmologic findings included markedly reduced visual acuity, bull's eye maculopathy, foveal hyperpigmentation, peripapillary atrophy, dyschromatopsia, extinguished photopic responses, and reduced scotopic responses observed on electroretinography consistent with the CRD phenotype often associated with ABCA4 mutations. Although no ABCA4 mutations were detected in either patient, whole-exome sequencing analysis identified 2 new homozygous mutations in the recently described RAB28 gene, the c.172 + 1G>C splice site variant in IVS2 and the missense c.T651G:p.C217W substitution. Both variants were determined as deleterious by predictive programs and were segregated with the disease in both families. Sequencing of 107 additional patients of Spanish descent with CRD did not reveal other cases with RAB28 mutations. CONCLUSIONS AND RELEVANCE: Deleterious mutations in RAB28 result in a classic CRD phenotype and are an infrequent cause of CRD in the Spanish population.
Keywords: Adolescent; Adult; Child; Diagnosis, Differential; DNA Mutational Analysis; Female; Follow-Up Studies; Genetic Predisposition to Disease; Hispanic Americans; Humans; Male; Microscopy, Acoustic; Mutation; Pedigree; Phenotype; rab GTP-Binding Proteins; Retinitis Pigmentosa; Retrospective Studies; Young Adult

New tools for Mendelian disease gene identification: PhenoDB variant analysis module; and GeneMatcher, a web-based tool for linking investigators with an interest in the same gene. - Sobreira, Nara; Schiettecatte, François; Boehm, Corinne; Valle, David; Hamosh, Ada (Hum Mutat, 2015)
Identifying the causative variant from among the thousands identified by whole-exome sequencing or whole-genome sequencing is a formidable challenge. To make this process as efficient and flexible as possible, we have developed a Variant Analysis Module coupled to our previously described Web-based phenotype intake tool, PhenoDB (http://researchphenodb.net and http://phenodb.org). When a small number of candidate-causative variants have been identified in a study of a particular patient or family, a second, more difficult challenge becomes proof of causality for any given variant. One approach to this problem is to find other cases with a similar phenotype and mutations in the same candidate gene. Alternatively, it may be possible to develop biological evidence for causality, an approach that is assisted by making connections to basic scientists studying the gene of interest, often in the setting of a model organism. Both of these strategies benefit from an open access, online site where individual clinicians and investigators could post genes of interest. To this end, we developed GeneMatcher (http://genematcher.org), a freely accessible Website that enables connections between clinicians and researchers across the world who share an interest in the same gene(s).
Keywords: Computational Biology; Databases, Genetic; Genetic Association Studies; Genetic Diseases, Inborn; Genetic Variation; Genomics; Internet; Phenotype; Software; Web Browser

NGLY1 mutation causes neuromotor impairment, intellectual disability, and neuropathy. - Çağlayan, Ahmet Okay; Comu, Sinan; Baranoski, Jacob F; Parman, Yesim; Kaymakçalan, Hande; Akgümüş, Gözde Tuğce; Caglar, Caner; Dölen, Duygu; Erson-Omay, Emine Zeynep; Harmanci, Akdes Serin; Mishra-Gorur, Ketu; Freeze, Hudson H; et al. (Eur J Med Genet, 2015)
N-glycanase 1 (NGLY1) is a conserved enzyme that is responsible for the deglycosylation of misfolded N-glycosylated proteins in the cytoplasm prior to their proteasome-mediated degradation. Disruption of this degradation process has been associated with various neurologic diseases including amyotrophic lateral sclerosis and Parkinson's disease. Here, we describe two siblings with neuromotor impairment, apparent intellectual disability, corneal opacities, and neuropathy who were found to possess a novel homozygous frame-shift mutation due to a 4 base pair deletion in NGLY1 (c.1533_1536delTCAA, p.Asn511LysfsX51). We hypothesize that this mutation likely limits the capability of neuronal cells to respond to stress due to accumulation of misfolded proteins, thereby impairing their survival and resulting in progressive loss of neurological function.
Keywords: Abnormalities, Multiple; Adolescent; Child; Corneal Opacity; Developmental Disabilities; Female; Frameshift Mutation; Genotype; Humans; Intellectual Disability; Male; Movement Disorders; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Peripheral Nervous System Diseases

Non-coding genetic variants in human disease. - Zhang, Feng; Lupski, James R (Hum Mol Genet, 2015)
Genetic variants, including single-nucleotide variants (SNVs) and copy number variants (CNVs), in the non-coding regions of the human genome can play an important role in human traits and complex diseases. Most of the genome-wide association study (GWAS) signals map to non-coding regions and potentially point to non-coding variants, whereas their functional interpretation is challenging. In this review, we discuss the human non-coding variants and their contributions to human diseases in the following four parts. (i) Functional annotations of non-coding SNPs mapped by GWAS: we discuss recent progress revealing some of the molecular mechanisms for GWAS signals affecting gene function. (ii) Technical progress in interpretation of non-coding variants: we briefly describe some of the technologies for functional annotations of non-coding variants, including the methods for genome-wide mapping of chromatin interaction, computational tools for functional predictions and the new genome editing technologies useful for dissecting potential functional consequences of non-coding variants. (iii) Non-coding CNVs in human diseases: we review our emerging understanding the role of non-coding CNVs in human disease. (iv) Compound inheritance of large genomic deletions and non-coding variants: compound inheritance at a locus consisting of coding variants plus non-coding ones is described.
Keywords: Animals; Disease; DNA Copy Number Variations; Genetic Variation; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Regulatory Sequences, Nucleic Acid

Nonrecurrent 17p11.2p12 Rearrangement Events that Result in Two Concomitant Genomic Disorders: The PMP22-RAI1 Contiguous Gene Duplication Syndrome. - Yuan, Bo; Harel, Tamar; Gu, Shen; Liu, Pengfei; Burglen, Lydie; Chantot-Bastaraud, Sandra; Gelowani, Violet; Beck, Christine R; Carvalho, Claudia M B; Cheung, Sau Wai; Coe, Andrew; Malan, Valérie; et al. (Am J Hum Genet, 2015)
The genomic duplication associated with Potocki-Lupski syndrome (PTLS) maps in close proximity to the duplication associated with Charcot-Marie-Tooth disease type 1A (CMT1A). PTLS is characterized by hypotonia, failure to thrive, reduced body weight, intellectual disability, and autistic features. CMT1A is a common autosomal dominant distal symmetric peripheral polyneuropathy. The key dosage-sensitive genes RAI1 and PMP22 are respectively associated with PTLS and CMT1A. Recurrent duplications accounting for the majority of subjects with these conditions are mediated by nonallelic homologous recombination between distinct low-copy repeat (LCR) substrates. The LCRs flanking a contiguous genomic interval encompassing both RAI1 and PMP22 do not share extensive homology; thus, duplications encompassing both loci are rare and potentially generated by a different mutational mechanism. We characterized genomic rearrangements that simultaneously duplicate PMP22 and RAI1, including nine potential complex genomic rearrangements, in 23 subjects by high-resolution array comparative genomic hybridization and breakpoint junction sequencing. Insertions and microhomologies were found at the breakpoint junctions, suggesting potential replicative mechanisms for rearrangement formation. At the breakpoint junctions of these nonrecurrent rearrangements, enrichment of repetitive DNA sequences was observed, indicating that they might predispose to genomic instability and rearrangement. Clinical evaluation revealed blended PTLS and CMT1A phenotypes with a potential earlier onset of neuropathy. Moreover, additional clinical findings might be observed due to the extra duplicated material included in the rearrangements. Our genomic analysis suggests replicative mechanisms as a predominant mechanism underlying PMP22-RAI1 contiguous gene duplications and provides further evidence supporting the role of complex genomic architecture in genomic instability.
Keywords: Abnormalities, Multiple; Charcot-Marie-Tooth Disease; Child; Child, Preschool; Chromosome Disorders; Chromosome Duplication; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; Female; Follow-Up Studies; Gene Duplication; Gene Rearrangement; Genome, Human; Genomics; Humans; Infant; Male; Models, Genetic; Myelin Proteins; Phenotype; Prognosis; Recombination, Genetic; Transcription Factors

Novel COL2A1 variant (c.619G>A, p.Gly207Arg) manifesting as a phenotype similar to progressive pseudorheumatoid dysplasia and spondyloepiphyseal dysplasia, Stanescu type. - Jurgens, Julie; Sobreira, Nara; Modaff, Peggy; Reiser, Catherine A; Seo, Soo Hyun; Seong, Moon-Woo; Park, Sung Sup; Kim, Ok Hwa; Cho, Tae-Joon; Pauli, Richard M (Hum Mutat, 2015)
Progressive pseudorheumatoid dysplasia (PPRD) is a rare, autosomal-recessive condition characterized by mild spondyloepiphyseal dysplasia (SED) and severe, progressive, early-onset arthritis due to WISP3 mutations. SED, Stanescu type, is a vaguely delineated autosomal-dominant dysplasia of unknown genetic etiology. Here, we report three individuals from two unrelated families with radiological features similar to PPRD and SED, Stanescu type who share the same novel COL2A1 variant and were matched following discussion at an academic conference. In the first family, we performed whole-exome sequencing on three family members, two of whom have a PPRD-like phenotype, and identified a heterozygous variant (c.619G>A, p.Gly207Arg) in both affected individuals. Independently, targeted sequencing of the COL2A1 gene in an unrelated proband with a similar phenotype identified the same heterozygous variant. We suggest that the p.Gly207Arg variant causes a distinct type II collagenopathy with features of PPRD and SED, Stanescu type.
Keywords: Adolescent; Adult; Child; Collagen Type II; Exome; Female; Humans; Joint Diseases; Male; Osteochondrodysplasias; Pedigree; Polymorphism, Single Nucleotide; Radiography; Sequence Analysis, DNA

PacBio-LITS: a large-insert targeted sequencing method for characterization of human disease-associated chromosomal structural variations. - Wang, Min; Beck, Christine R; English, Adam C; Meng, Qingchang; Buhay, Christian; Han, Yi; Doddapaneni, Harsha V; Yu, Fuli; Boerwinkle, Eric; Lupski, James R; Muzny, Donna M; Gibbs, Richard A (BMC Genomics, 2015)
BACKGROUND: Generation of long (>5 Kb) DNA sequencing reads provides an approach for interrogation of complex regions in the human genome. Currently, large-insert whole genome sequencing (WGS) technologies from Pacific Biosciences (PacBio) enable analysis of chromosomal structural variations (SVs), but the cost to achieve the required sequence coverage across the entire human genome is high. RESULTS: We developed a method (termed PacBio-LITS) that combines oligonucleotide-based DNA target-capture enrichment technologies with PacBio large-insert library preparation to facilitate SV studies at specific chromosomal regions. PacBio-LITS provides deep sequence coverage at the specified sites at substantially reduced cost compared with PacBio WGS. The efficacy of PacBio-LITS is illustrated by delineating the breakpoint junctions of low copy repeat (LCR)-associated complex structural rearrangements on chr17p11.2 in patients diagnosed with Potocki-Lupski syndrome (PTLS; MIM#610883). We successfully identified previously determined breakpoint junctions in three PTLS cases, and also were able to discover novel junctions in repetitive sequences, including LCR-mediated breakpoints. The new information has enabled us to propose mechanisms for formation of these structural variants. CONCLUSIONS: The new method leverages the cost efficiency of targeted capture-sequencing as well as the mappability and scaffolding capabilities of long sequencing reads generated by the PacBio platform. It is therefore suitable for studying complex SVs, especially those involving LCRs, inversions, and the generation of chimeric Alu elements at the breakpoints. Other genomic research applications, such as haplotype phasing and small insertion and deletion validation could also benefit from this technology.
Keywords: Chromosome Aberrations; Gene Library; Gene Rearrangement; Genetic Association Studies; Genomics; High-Throughput Nucleotide Sequencing; Humans; Workflow

Rare A2ML1 variants confer susceptibility to otitis media. - Santos-Cortez, Regie Lyn P; Chiong, Charlotte M; Reyes-Quintos, Ma Rina T; Tantoco, Ma Leah C; Wang, Xin; Acharya, Anushree; Abbe, Izoduwa; Giese, Arnaud P; Smith, Joshua D; Allen, E Kaitlynn; Li, Biao; Cutiongco-de la Paz, Eva Maria; et al. (Nat Genet, 2015)
A duplication variant within the middle ear-specific gene A2ML1 cosegregates with otitis media in an indigenous Filipino pedigree (LOD score = 7.5 at reduced penetrance) and lies within a founder haplotype that is also shared by 3 otitis-prone European-American and Hispanic-American children but is absent in non-otitis-prone children and >62,000 next-generation sequences. We identified seven additional A2ML1 variants in six otitis-prone children. Collectively, our studies support a role for A2ML1 in the pathophysiology of otitis media.
Keywords: alpha-Macroglobulins; Animals; Base Sequence; Child; Cochlea; Exome; Family Health; Female; Gene Duplication; Gene Frequency; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Male; Mice, Inbred C57BL; Models, Molecular; Otitis Media; Pedigree; Principal Component Analysis; Protein Conformation; Sequence Analysis, DNA

Rare variants in RTEL1 are associated with familial interstitial pneumonia. - Cogan, Joy D; Kropski, Jonathan A; Zhao, Min; Mitchell, Daphne B; Rives, Lynette; Markin, Cheryl; Garnett, Errine T; Montgomery, Keri H; Mason, Wendi R; McKean, David F; Powers, Julia; Murphy, Elissa; et al. (Am J Respir Crit Care Med, 2015)
RATIONALE: Up to 20% of cases of idiopathic interstitial pneumonia cluster in families, comprising the syndrome of familial interstitial pneumonia (FIP); however, the genetic basis of FIP remains uncertain in most families. OBJECTIVES: To determine if new disease-causing rare genetic variants could be identified using whole-exome sequencing of affected members from FIP families, providing additional insights into disease pathogenesis. METHODS: Affected subjects from 25 kindreds were selected from an ongoing FIP registry for whole-exome sequencing from genomic DNA. Candidate rare variants were confirmed by Sanger sequencing, and cosegregation analysis was performed in families, followed by additional sequencing of affected individuals from another 163 kindreds. MEASUREMENTS AND MAIN RESULTS: We identified a potentially damaging rare variant in the gene encoding for regulator of telomere elongation helicase 1 (RTEL1) that segregated with disease and was associated with very short telomeres in peripheral blood mononuclear cells in 1 of 25 families in our original whole-exome sequencing cohort. Evaluation of affected individuals in 163 additional kindreds revealed another eight families (4.7%) with heterozygous rare variants in RTEL1 that segregated with clinical FIP. Probands and unaffected carriers of these rare variants had short telomeres (<10% for age) in peripheral blood mononuclear cells and increased T-circle formation, suggesting impaired RTEL1 function. CONCLUSIONS: Rare loss-of-function variants in RTEL1 represent a newly defined genetic predisposition for FIP, supporting the importance of telomere-related pathways in pulmonary fibrosis.
Keywords: Aged; Aged, 80 and over; DNA Helicases; Female; Genetic Variation; Heterozygote; Humans; Lung; Lung Diseases, Interstitial; Male; Middle Aged; Pedigree; Telomere

Rare variants in the notch signaling pathway describe a novel type of autosomal recessive Klippel-Feil syndrome. - Karaca, Ender; Yuregir, Ozge O; Bozdogan, Sevcan T; Aslan, Huseyin; Pehlivan, Davut; Jhangiani, Shalini N; Akdemir, Zeynep C; Gambin, Tomasz; Bayram, Yavuz; Atik, Mehmed M; Erdin, Serkan; Muzny, Donna; et al. (Am J Med Genet A, 2015)
Klippel-Feil syndrome is a rare disorder represented by a subgroup of segmentation defects of the vertebrae and characterized by fusion of the cervical vertebrae, low posterior hairline, and short neck with limited motion. Both autosomal dominant and recessive inheritance patterns were reported in families with Klippel-Feil. Mutated genes for both dominant (GDF6 and GDF3) and recessive (MEOX1) forms of Klippel-Feil syndrome have been shown to be involved in somite development via transcription regulation and signaling pathways. Heterotaxy arises from defects in proteins that function in the development of left-right asymmetry of the developing embryo. We describe a consanguineous family with a male proband who presents with classical Klippel-Feil syndrome together with heterotaxy (situs inversus totalis). The present patient also had Sprengel's deformity, deformity of the sternum, and a solitary kidney. Using exome sequencing, we identified a homozygous frameshift mutation (c.299delT; p.L100fs) in RIPPLY2, a gene shown to play a crucial role in somitogenesis and participate in the Notch signaling pathway via negatively regulating Tbx6. Our data confirm RIPPLY2 as a novel gene for autosomal recessive Klippel-Feil syndrome, and in addition-from a mechanistic standpoint-suggest the possibility that mutations in RIPPLY2 could also lead to heterotaxy. © 2015 Wiley Periodicals, Inc.
Keywords: Adolescent; Base Sequence; Female; Humans; Klippel-Feil Syndrome; Male; Molecular Sequence Data; Mutation; Pedigree; Radiography; Receptors, Notch; Signal Transduction; Spine

Reads meet rotamers: structural biology in the age of deep sequencing. - Sethi, Anurag; Clarke, Declan; Chen, Jieming; Kumar, Sushant; Galeev, Timur R; Regan, Lynne; Gerstein, Mark (Curr Opin Struct Biol, 2015)
Structure has traditionally been interrelated with sequence, usually in the framework of comparing sequences across species sharing a common fold. However, the nature of information within the sequence and structure databases is evolving, changing the type of comparisons possible. In particular, we now have a vast amount of personal genome sequences from human populations and a greater fraction of new structures contain interacting proteins within large complexes. Consequently, we have to recast our conception of sequence conservation and its relation to structure-for example, focusing more on selection within the human population. Moreover, within structural biology there is less emphasis on the discovery of novel folds and more on relating structures to networks of protein interactions. We cover this changing mindset here.
Keywords: High-Throughput Nucleotide Sequencing; Humans; Isomerism; Mutation; Proteins

Recurrent gain of function mutation in calcium channel CACNA1H causes early-onset hypertension with primary aldosteronism. - Scholl, Ute I; Stölting, Gabriel; Nelson-Williams, Carol; Vichot, Alfred A; Choi, Murim; Loring, Erin; Prasad, Manju L; Goh, Gerald; Carling, Tobias; Juhlin, C Christofer; Quack, Ivo; Rump, Lars C; et al. (Elife, 2015)
Many Mendelian traits are likely unrecognized owing to absence of traditional segregation patterns in families due to causation by de novo mutations, incomplete penetrance, and/or variable expressivity. Genome-level sequencing can overcome these complications. Extreme childhood phenotypes are promising candidates for new Mendelian traits. One example is early onset hypertension, a rare form of a global cause of morbidity and mortality. We performed exome sequencing of 40 unrelated subjects with hypertension due to primary aldosteronism by age 10. Five subjects (12.5%) shared the identical, previously unidentified, heterozygous CACNA1H(M1549V) mutation. Two mutations were demonstrated to be de novo events, and all mutations occurred independently. CACNA1H encodes a voltage-gated calcium channel (CaV3.2) expressed in adrenal glomerulosa. CACNA1H(M1549V) showed drastically impaired channel inactivation and activation at more hyperpolarized potentials, producing increased intracellular Ca(2+), the signal for aldosterone production. This mutation explains disease pathogenesis and provides new insight into mechanisms mediating aldosterone production and hypertension.
Keywords: Adolescent; Adult; Age of Onset; Aldosterone; Amino Acid Sequence; Calcium; Calcium Channels, T-Type; Calcium Signaling; Child; Child, Preschool; Female; Gene Expression; Genotype; Heterozygote; Humans; Hyperaldosteronism; Hypertension; Infant; Male; Membrane Potentials; Middle Aged; Molecular Sequence Data; Mutation; Phenotype; Recurrence; Sequence Alignment; Zona Glomerulosa

Root anomalies and dentin dysplasia in autosomal recessive hyperphosphatemic familial tumoral calcinosis (HFTC). - Vieira, Alexandre R; Lee, Moses; Vairo, Filippo; Loguercio Leite, Julio Cesar; Munerato, Maria Cristina; Visioli, Fernanda; D'Ávila, Stéphanie Rodrigues; Wang, Shih-Kai; Choi, Murim; Simmer, James P; Hu, Jan C-C (Oral Surg Oral Med Oral Pathol Oral Radiol, 2015)
Hyperphosphatemic familial tumoral calcinosis (HFTC, OMIM #211900) is an autosomal recessive metabolic disorder characterized by hyperphosphatemia, tooth root defects, and the progressive deposition of calcium phosphate crystals in periarticular spaces, soft tissues, and sometimes bone.(1) In this HFTC case report, we document the dental phenotype associated with a homozygous missense mutation (g.29077 C>T; c.484 C>T; p.Arg162*) in GALNT3 (OMIM 6017563), a gene encoding UDP-GalNAc transferase 3 that catalyzes the first step of O-linked oligosaccharide biosynthesis in the Golgi. The medical and dental pathology is believed to be caused primarily by high serum phosphate levels (hyperphosphatemia), which, in turn, is caused by failure of GALNT3 to glycosylate the phosphate regulator protein FGF23, impairing its ability inhibit reabsorption of filtered phosphate in the kidneys.
Keywords: Adolescent; Calcinosis; Dentin Dysplasia; Humans; Hyperostosis, Cortical, Congenital; Hyperphosphatemia; Male; Mutation, Missense; N-Acetylgalactosaminyltransferases; Pedigree; Phenotype; Radiography, Panoramic; Tooth Root

Safety and Proof-of-Concept Study of Oral QLT091001 in Retinitis Pigmentosa Due to Inherited Deficiencies of Retinal Pigment Epithelial 65 Protein (RPE65) or Lecithin:Retinol Acyltransferase (LRAT). - Scholl, Hendrik P N; Moore, Anthony T; Koenekoop, Robert K; Wen, Yuquan; Fishman, Gerald A; van den Born, L Ingeborgh; Bittner, Ava; Bowles, Kristen; Fletcher, Emily C; Collison, Frederick T; Dagnelie, Gislin; Degli Eposti, Simona; et al. (PLoS One, 2015)
UNLABELLED: Restoring vision in inherited retinal degenerations remains an unmet medical need. In mice exhibiting a genetically engineered block of the visual cycle, vision was recently successfully restored by oral administration of 9-cis-retinyl acetate (QLT091001). Safety and visual outcomes of a once-daily oral dose of 40 mg/m2/day QLT091001 for 7 consecutive days was investigated in an international, multi-center, open-label, proof-of-concept study in 18 patients with RPE65- or LRAT-related retinitis pigmentosa. Eight of 18 patients (44%) showed a ≥20% increase and 4 of 18 (22%) showed a ≥40% increase in functional retinal area determined from Goldmann visual fields; 12 (67%) and 5 (28%) of 18 patients showed a ≥5 and ≥10 ETDRS letter score increase of visual acuity, respectively, in one or both eyes at two or more visits within 2 months of treatment. In two patients who underwent fMRI, a significant positive response was measured to stimuli of medium contrast, moving, pattern targets in both left and right hemispheres of the occipital cortex. There were no serious adverse events. Treatment-related adverse events were transient and the most common included headache, photophobia, nausea, vomiting, and minor biochemical abnormalities. Measuring the outer segment length of the photoreceptor layer with high-definition optical coherence tomography was highly predictive of treatment responses with responders having a significantly larger baseline outer segment thickness (11.7 ± 4.8 μm, mean ± 95% CI) than non-responders (3.5 ± 1.2 μm). This structure-function relationship suggests that treatment with QLT091001 is more likely to be efficacious if there is sufficient photoreceptor integrity. TRIAL REGISTRATION: ClinicalTrials.gov NCT01014052.
Keywords: Acyltransferases; Administration, Oral; Adult; Anticarcinogenic Agents; Cerebral Cortex; Child; cis-trans-Isomerases; Drug Dosage Calculations; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Radiography; Retinal Ganglion Cells; Retinal Neurons; Retinitis Pigmentosa; Treatment Outcome; Visual Acuity; Visual Fields; Vitamin A; Young Adult

A second locus for Schneckenbecken dysplasia identified by a mutation in the gene encoding inositol polyphosphate phosphatase-like 1 (INPPL1). - Lee, Hane; Nevarez, Lisette; Lachman, Ralph S; Wilcox, William R; Krakow, Deborah; Cohn, Daniel H (Am J Med Genet A, 2015)
Keywords: Exome; Gene Expression; Genetic Loci; Gestational Age; Homozygote; Humans; Hydrops Fetalis; Infant, Newborn; Male; Mutation; Osteochondrodysplasias; Phosphatidylinositol-3,4,5-Trisphosphate 5-Phosphatases; Phosphoric Monoester Hydrolases; Stillbirth

Secondary findings and carrier test frequencies in a large multiethnic sample. - Gambin, Tomasz; Jhangiani, Shalini N; Below, Jennifer E; Campbell, Ian M; Wiszniewski, Wojciech; Muzny, Donna M; Staples, Jeffrey; Morrison, Alanna C; Bainbridge, Matthew N; Penney, Samantha; McGuire, Amy L; Gibbs, Richard A; et al. (Genome Med, 2015)
BACKGROUND: Besides its growing importance in clinical diagnostics and understanding the genetic basis of Mendelian and complex diseases, whole exome sequencing (WES) is a rich source of additional information of potential clinical utility for physicians, patients and their families. We analyzed the frequency and nature of single nucleotide variants (SNVs) considered secondary findings and recessive disease allele carrier status in the exomes of 8554 individuals from a large, randomly sampled cohort study and 2514 patients from a study of presumed Mendelian disease having undergone WES. METHODS: We used the same sequencing platform and data processing pipeline to analyze all samples and characterized the distributions of reported pathogenic (ClinVar, Human Gene Mutation Database (HGMD)) and predicted deleterious variants in the pre-specified American College of Medical Genetics and Genomics (ACMG) secondary findings and recessive disease genes in different ethnic groups. RESULTS: In the 56 ACMG secondary findings genes, the average number of predicted deleterious variants per individual was 0.74, and the mean number of ClinVar reported pathogenic variants was 0.06. We observed an average of 10 deleterious and 0.78 ClinVar reported pathogenic variants per individual in 1423 autosomal recessive disease genes. By repeatedly sampling pairs of exomes, 0.5 % of the randomly generated couples were at 25 % risk of having an affected offspring for an autosomal recessive disorder based on the ClinVar variants. CONCLUSIONS: By investigating reported pathogenic and novel, predicted deleterious variants we estimated the lower and upper limits of the population fraction for which exome sequencing may reveal additional medically relevant information. We suggest that the observed wide range for the lower and upper limits of these frequency numbers will be gradually reduced due to improvement in classification databases and prediction algorithms.

An siRNA-based functional genomics screen for the identification of regulators of ciliogenesis and ciliopathy genes. - Wheway, Gabrielle; Schmidts, Miriam; Mans, Dorus A; Szymanska, Katarzyna; Nguyen, Thanh-Minh T; Racher, Hilary; Phelps, Ian G; Toedt, Grischa; Kennedy, Julie; Wunderlich, Kirsten A; Sorusch, Nasrin; Abdelhamed, Zakia A; et al. (Nat Cell Biol, 2015)
Defects in primary cilium biogenesis underlie the ciliopathies, a growing group of genetic disorders. We describe a whole-genome siRNA-based reverse genetics screen for defects in biogenesis and/or maintenance of the primary cilium, obtaining a global resource. We identify 112 candidate ciliogenesis and ciliopathy genes, including 44 components of the ubiquitin-proteasome system, 12 G-protein-coupled receptors, and 3 pre-mRNA processing factors (PRPF6, PRPF8 and PRPF31) mutated in autosomal dominant retinitis pigmentosa. The PRPFs localize to the connecting cilium, and PRPF8- and PRPF31-mutated cells have ciliary defects. Combining the screen with exome sequencing data identified recessive mutations in PIBF1, also known as CEP90, and C21orf2, also known as LRRC76, as causes of the ciliopathies Joubert and Jeune syndromes. Biochemical approaches place C21orf2 within key ciliopathy-associated protein modules, offering an explanation for the skeletal and retinal involvement observed in individuals with C21orf2 variants. Our global, unbiased approaches provide insights into ciliogenesis complexity and identify roles for unanticipated pathways in human genetic disease.
Keywords: Abnormalities, Multiple; Animals; Caenorhabditis elegans; Cerebellar Diseases; Cerebellum; Cilia; Ciliary Motility Disorders; Databases, Genetic; Ellis-Van Creveld Syndrome; Eye Abnormalities; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Genomics; HEK293 Cells; High-Throughput Nucleotide Sequencing; Humans; Kidney Diseases, Cystic; Membrane Proteins; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Photoreceptor Cells; Pregnancy Proteins; Proteins; Reproducibility of Results; Retina; RNA Interference; Suppressor Factors, Immunologic; Transfection; Zebrafish

Somatic Activating RAS Mutations Cause Vascular Tumors Including Pyogenic Granuloma. - Lim, Young H; Douglas, Stephanie R; Ko, Christine J; Antaya, Richard J; McNiff, Jennifer M; Zhou, Jing; Choate, Keith A; Narayan, Deepak (J Invest Dermatol, 2015)
Keywords: Adolescent; Cell Proliferation; Child; Child, Preschool; Female; Gene Expression Regulation, Neoplastic; Granuloma, Pyogenic; Humans; Infant; Infant, Newborn; Male; Mutation; ras Proteins; Vascular Neoplasms

Somatic mosaicism: implications for disease and transmission genetics. - Campbell, Ian M; Shaw, Chad A; Stankiewicz, Pawel; Lupski, James R (Trends Genet, 2015)
Nearly all of the genetic material among cells within an organism is identical. However, single-nucleotide variants (SNVs), small insertions/deletions (indels), copy-number variants (CNVs), and other structural variants (SVs) continually accumulate as cells divide during development. This process results in an organism composed of countless cells, each with its own unique personal genome. Thus, every human is undoubtedly mosaic. Mosaic mutations can go unnoticed, underlie genetic disease or normal human variation, and may be transmitted to the next generation as constitutional variants. We review the influence of the developmental timing of mutations, the mechanisms by which they arise, methods for detecting mosaic variants, and the risk of passing these mutations on to the next generation.
Keywords: Animals; Genetic Diseases, Inborn; Genome, Human; Humans; Mosaicism; Mutagenesis, Insertional; Mutation; Polymorphism, Single Nucleotide; Risk; Trinucleotide Repeat Expansion

Somatic p.T771R KDR (VEGFR2) Mutation Arising in a Sporadic Angioma During Ramucirumab Therapy. - Lim, Young H; Odell, Ian D; Ko, Christine J; Choate, Keith A (JAMA Dermatol, 2015)
IMPORTANCE: Inhibition of angiogenesis is an effective anticancer strategy because neoplasms require a rich blood supply. Ramucirumab, approved by the US Food and Drug Administration in 2014 to treat gastric adenocarcinomas and non-small cell lung carcinomas, targets vascular endothelial growth factor 2 (VEGFR2). We identified a patient prescribed a regimen of irinotecan hydrochloride, cetuximab, and ramucirumab for metastatic rectal cancer (diagnosed in November 2013 and treated through early January 2015) who developed a new-onset, expanding vascular lesion on his right leg. Via exome sequencing, we found that the lesion contained a single somatic mutation in KDR (encodes VEGFR2), possibly in response to ramucirumab. Vascular tumors are not a known complication of antiangiogenic therapeutics. OBSERVATIONS: Exome sequencing of the well-demarcated, blanching vascular lesion on the lateral right shin revealed a somatic p.T771R mutation in KDR, without evidence of other somatic mutations or loss of heterozygosity. Histological features included lobules of small vessels within the dermis, resembling a tufted angioma. CONCLUSIONS AND RELEVANCE: A potential adverse effect of ramucirumab in combination therapy is the development of sporadic angiomas. The p.T771R mutation was previously implicated in autophosphorylation of VEGFR2 and reported in angiosarcomas alongside other driver mutations. Our observations suggest that this mutation confers a proliferative advantage in the setting of ramucirumab therapy. Patients receiving ramucirumab should be monitored for the development of new vascular lesions.
Keywords: Adult; Angiogenesis Inhibitors; Antibodies, Monoclonal; Antineoplastic Combined Chemotherapy Protocols; Camptothecin; Cetuximab; Hemangioma; Humans; Irinotecan; Male; Mutation; Rectal Neoplasms; Skin Neoplasms; Vascular Endothelial Growth Factor Receptor-2

Somatic V600E BRAF Mutation in Linear and Sporadic Syringocystadenoma Papilliferum. - Levinsohn, Jonathan L; Sugarman, Jeffrey L; Bilguvar, Kaya; McNiff, Jennifer M; Choate, Keith A (J Invest Dermatol, 2015)
Keywords: Biopsy, Needle; Child; Cystadenoma; Female; Gene Expression Regulation, Neoplastic; Humans; Immunohistochemistry; Mutation; Proto-Oncogene Proteins B-raf; Sweat Gland Neoplasms; Syringoma

Structural variation mutagenesis of the human genome: Impact on disease and evolution. - Lupski, James R (Environ Mol Mutagen, 2015)
Watson-Crick base-pair changes, or single-nucleotide variants (SNV), have long been known as a source of mutations. However, the extent to which DNA structural variation, including duplication and deletion copy number variants (CNV) and copy number neutral inversions and translocations, contribute to human genome variation and disease has been appreciated only recently. Moreover, the potential complexity of structural variants (SV) was not envisioned; thus, the frequency of complex genomic rearrangements and how such events form remained a mystery. The concept of genomic disorders, diseases due to genomic rearrangements and not sequence-based changes for which genomic architecture incite genomic instability, delineated a new category of conditions distinct from chromosomal syndromes and single-gene Mendelian diseases. Nevertheless, it is the mechanistic understanding of CNV/SV formation that has promoted further understanding of human biology and disease and provided insights into human genome and gene evolution. Environ. Mol. Mutagen. 56:419-436, 2015. © 2015 Wiley Periodicals, Inc.
Keywords: Animals; Evolution, Molecular; Gene Dosage; Genetic Predisposition to Disease; Genome, Human; Genomic Structural Variation; Humans; Mutagenesis

Successful diagnosis of HIBCH deficiency from exome sequencing and positive retrospective analysis of newborn screening cards in two siblings presenting with Leigh's disease. - Stiles, Ashlee R; Ferdinandusse, Sacha; Besse, Arnaud; Appadurai, Vivek; Leydiker, Karen B; Cambray-Forker, E J; Bonnen, Penelope E; Abdenur, Jose E (Mol Genet Metab, 2015)
PURPOSE: 3-Hydroxyisobutryl-CoA hydrolase (HIBCH) deficiency is a rare disorder of valine metabolism. We present a family with the oldest reported subjects with HIBCH deficiency and provide support that HIBCH deficiency should be included in the differential for elevated hydroxy-C4-carnitine in newborn screening (NBS). METHODS: Whole exome sequencing (WES) was performed on one affected sibling. HIBCH enzymatic activity was measured in patient fibroblasts. Acylcarnitines were measured by electrospray ionization tandem mass spectrometry (ESI-MS/MS). Disease incidence was estimated using a cohort of 61,434 individuals. RESULTS: Two siblings presented with infantile-onset, progressive neurodegenerative disease. WES identified a novel homozygous variant in HIBCH c.196C>T; p.Arg66Trp. HIBCH enzymatic activity was significantly reduced in patients' fibroblasts. Acylcarnitine analysis showed elevated hydroxy-C4-carnitine in blood spots of both affected siblings, including in their NBS cards, while plasma acylcarnitines were normal. Estimates show HIBCH deficiency incidence as high as 1 in ~130,000 individuals. CONCLUSION: We describe a novel family with HIBCH deficiency at the biochemical, enzymatic and molecular level. Disease incidence estimates indicate HIBCH deficiency may be under-diagnosed. This together with the elevated hydroxy-C4-carnitine found in the retrospective analysis of our patient's NBS cards suggests that this disorder could be screened for by NBS programs and should be added to the differential diagnosis for elevated hydroxy-C4-carnitine which is already measured in most NBS programs using MS/MS.
Keywords: Abnormalities, Multiple; Adolescent; Amino Acid Metabolism, Inborn Errors; Carnitine; Child; Child, Preschool; Cohort Studies; Exome; Female; Fibroblasts; Humans; Infant; Infant, Newborn; Leigh Disease; Male; Mass Spectrometry; Neonatal Screening; Prognosis; Retrospective Studies; Sequence Analysis, DNA; Siblings; Thiolester Hydrolases

TBX6 null variants and a common hypomorphic allele in congenital scoliosis. - Wu, N; Ming, X; Xiao, J; Wu, Z; Chen, X; Shinawi, M; Shen, Y; Yu, G; Liu, J; Xie, H; Gucev, Z S; Liu, S; et al. (N Engl J Med, 2015)
BACKGROUND: Congenital scoliosis is a common type of vertebral malformation. Genetic susceptibility has been implicated in congenital scoliosis. METHODS: We evaluated 161 Han Chinese persons with sporadic congenital scoliosis, 166 Han Chinese controls, and 2 pedigrees, family members of which had a 16p11.2 deletion, using comparative genomic hybridization, quantitative polymerase-chain-reaction analysis, and DNA sequencing. We carried out tests of replication using an additional series of 76 Han Chinese persons with congenital scoliosis and a multicenter series of 42 persons with 16p11.2 deletions. RESULTS: We identified a total of 17 heterozygous TBX6 null mutations in the 161 persons with sporadic congenital scoliosis (11%); we did not observe any null mutations in TBX6 in 166 controls (P<3.8×10(-6)). These null alleles include copy-number variants (12 instances of a 16p11.2 deletion affecting TBX6) and single-nucleotide variants (1 nonsense and 4 frame-shift mutations). However, the discordant intrafamilial phenotypes of 16p11.2 deletion carriers suggest that heterozygous TBX6 null mutation is insufficient to cause congenital scoliosis. We went on to identify a common TBX6 haplotype as the second risk allele in all 17 carriers of TBX6 null mutations (P<1.1×10(-6)). Replication studies involving additional persons with congenital scoliosis who carried a deletion affecting TBX6 confirmed this compound inheritance model. In vitro functional assays suggested that the risk haplotype is a hypomorphic allele. Hemivertebrae are characteristic of TBX6-associated congenital scoliosis. CONCLUSIONS: Compound inheritance of a rare null mutation and a hypomorphic allele of TBX6 accounted for up to 11% of congenital scoliosis cases in the series that we analyzed. (Funded by the National Basic Research Program of China and others.).
Keywords: Adolescent; Asian Continental Ancestry Group; Child; Child, Preschool; Chromosomes, Human, Pair 16; DNA Copy Number Variations; Female; Genetic Predisposition to Disease; Genotype; Humans; Male; Mutation; Pedigree; Phenotype; Radiography; Scoliosis; Sequence Deletion; Spine; T-Box Domain Proteins

Truncating mutations in the last exon of NOTCH3 cause lateral meningocele syndrome. - Gripp, Karen W; Robbins, Katherine M; Sobreira, Nara L; Witmer, P Dane; Bird, Lynne M; Avela, Kristiina; Mäkitie, Outi; Alves, Daniela; Hogue, Jacob S; Zackai, Elaine H; Doheny, Kimberly F; Stabley, Deborah L; et al. (Am J Med Genet A, 2015)
Lateral meningocele syndrome (LMS, OMIM%130720), also known as Lehman syndrome, is a very rare skeletal disorder with facial anomalies, hypotonia and meningocele-related neurologic dysfunction. The characteristic lateral meningoceles represent the severe end of the dural ectasia spectrum and are typically most severe in the lower spine. Facial features of LMS include hypertelorism and telecanthus, high arched eyebrows, ptosis, midfacial hypoplasia, micrognathia, high and narrow palate, low-set ears and a hypotonic appearance. Hyperextensibility, hernias and scoliosis reflect a connective tissue abnormality, and aortic dilation, a high-pitched nasal voice, wormian bones and osteolysis may be present. Lateral meningocele syndrome has phenotypic overlap with Hajdu-Cheney syndrome. We performed exome resequencing in five unrelated individuals with LMS and identified heterozygous truncating NOTCH3 mutations. In an additional unrelated individual Sanger sequencing revealed a deleterious variant in the same exon 33. In total, five novel de novo NOTCH3 mutations were identified in six unrelated patients. One had a 26 bp deletion (c.6461_6486del, p.G2154fsTer78), two carried the same single base pair insertion (c.6692_93insC, p.P2231fsTer11), and three individuals had a nonsense point mutation at c.6247A > T (pK2083*), c.6663C > G (p.Y2221*) or c.6732C > A, (p.Y2244*). All mutations cluster into the last coding exon, resulting in premature termination of the protein and truncation of the negative regulatory proline-glutamate-serine-threonine rich PEST domain. Our results suggest that mutant mRNA products escape nonsense mediated decay. The truncated NOTCH3 may cause gain-of-function through decreased clearance of the active intracellular product, resembling NOTCH2 mutations in the clinically related Hajdu-Cheney syndrome and contrasting the NOTCH3 missense mutations causing CADASIL.
Keywords: Abnormalities, Multiple; Child; Child, Preschool; DNA Mutational Analysis; Exome; Exons; Facies; High-Throughput Nucleotide Sequencing; Humans; Magnetic Resonance Imaging; Male; Meningocele; Mutation; Phenotype; Receptor, Notch3; Receptors, Notch; Young Adult

Whole Exome Sequencing Identifies an Adult-Onset Case of Methylmalonic Aciduria and Homocystinuria Type C (cblC) with Non-Syndromic Bull's Eye Maculopathy. - Collison, Frederick T; Xie, Yajing Angela; Gambin, Tomasz; Jhangiani, Shalini; Muzny, Donna; Gibbs, Richard; Lupski, James R; Fishman, Gerald A; Allikmets, Rando (Ophthalmic Genet, 2015)
BACKGROUND: Methylmalonic aciduria and homocystinuria type C (cblC), a disorder of vitamin B12 (cobalamin) metabolism caused by mutations in the MMACHC gene, presents with many systemic symptoms, including neurological, cognitive, psychiatric, and thromboembolic events. Retinal phenotypes, including maculopathy, pigmentary retinopathy, and optic atrophy are common in early onset form of the disease but are rare in adult onset forms. MATERIALS AND METHODS: An adult Hispanic female presented with decreased central vision, bilateral pericentral ring scotomas and bull's eye-appearing macular lesions at 28 years of age. Her medical history was otherwise unremarkable except for iron deficiency anemia and both urinary tract and kidney infections. Screening of the ABCA4 gene, mutations in which frequently cause bull's eye maculopathy, was negative. Subsequently, analysis with whole exome sequencing was performed. RESULTS: Whole exome sequencing discovered compound heterozygous mutations in MMACHC, c.G482A:p.Arg161Gln and c.270_271insA:p.Arg91Lysfs*14, which segregated with the disease in the family. The genetic diagnosis was confirmed by biochemical laboratory testing, showing highly elevated urine methylmalonic acid/creatinine and homocysteine levels, and suggesting disease management with hydroxycobalamin injections and carnitine supplementation. CONCLUSIONS: In summary, a unique case of an adult patient with bull's eye macular lesions and no clinically relevant systemic symptoms was diagnosed with cblC by genetic screening and follow-up biochemical laboratory tests.
Keywords: Adult; Carrier Proteins; Electroretinography; Exome; Female; Genetic Testing; Heterozygote; Homocystinuria; Humans; Macular Degeneration; Mutation; Pedigree; Scotoma; Sequence Analysis, DNA; Tomography, Optical Coherence; Visual Acuity; Visual Fields; Vitamin B 12; Vitamin B 12 Deficiency; Vitamin B Complex

Whole exome sequencing identifies de novo heterozygous CAV1 mutations associated with a novel neonatal onset lipodystrophy syndrome. - Garg, Abhimanyu; Kircher, Martin; Del Campo, Miguel; Amato, R Stephen; Agarwal, Anil K (Am J Med Genet A, 2015)
Despite remarkable progress in identifying causal genes for many types of genetic lipodystrophies in the last decade, the molecular basis of many extremely rare lipodystrophy patients with distinctive phenotypes remains unclear. We conducted whole exome sequencing of the parents and probands from six pedigrees with neonatal onset of generalized loss of subcutaneous fat with additional distinctive phenotypic features and report de novo heterozygous null mutations, c.424C>T (p.Q142*) and c.479_480delTT (p.F160*), in CAV1 in a 7-year-old male and a 3-year-old female of European origin, respectively. Both the patients had generalized fat loss, thin mottled skin and progeroid features at birth. The male patient had cataracts requiring extraction at age 30 months and the female patient had pulmonary arterial hypertension. Dermal fibroblasts of the female patient revealed negligible CAV1 immunofluorescence staining compared to control but there were no differences in the number and morphology of caveolae upon electron microscopy examination. Based upon the similarities in the clinical features of these two patients, previous reports of CAV1 mutations in patients with lipodystrophies and pulmonary hypertension, and similar features seen in CAV1 null mice, we conclude that these variants are the most likely cause of one subtype of neonatal onset generalized lipodystrophy syndrome.
Keywords: Caveolin 1; Cells, Cultured; Exome; Female; Heterozygote; Humans; Infant, Newborn; Lipodystrophy; Male; Mutation; Pedigree

Whole-exome sequencing identifies homozygous GPR161 mutation in a family with pituitary stalk interruption syndrome. - Karaca, Ender; Buyukkaya, Ramazan; Pehlivan, Davut; Charng, Wu-Lin; Yaykasli, Kursat O; Bayram, Yavuz; Gambin, Tomasz; Withers, Marjorie; Atik, Mehmed M; Arslanoglu, Ilknur; Bolu, Semih; Erdin, Serkan; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Pituitary stalk interruption syndrome (PSIS) is a rare, congenital anomaly of the pituitary gland characterized by pituitary gland insufficiency, thin or discontinuous pituitary stalk, anterior pituitary hypoplasia, and ectopic positioning of the posterior pituitary gland (neurohypophysis). The clinical presentation of patients with PSIS varies from isolated growth hormone (GH) deficiency to combined pituitary insufficiency and accompanying extrapituitary findings. Mutations in HESX1, LHX4, OTX2, SOX3, and PROKR2 have been associated with PSIS in less than 5% of cases; thus, the underlying genetic etiology for the vast majority of cases remains to be determined. OBJECTIVE: We applied whole-exome sequencing (WES) to a consanguineous family with two affected siblings who have pituitary gland insufficiency and radiographic findings of hypoplastic (thin) pituitary gland, empty sella, ectopic neurohypophysis, and interrupted pitiutary stalk-characteristic clinical diagnostic findings of PSIS. DESIGN AND PARTICIPANTS: WES was applied to two affected and one unaffected siblings. RESULTS: WES of two affected and one unaffected sibling revealed a unique homozygous missense mutation in GPR161, which encodes the orphan G protein-coupled receptor 161, a protein responsible for transducing extracellular signals across the plasma membrane into the cell. CONCLUSION: Mutations of GPR161 may be implicated as a potential novel cause of PSIS.
Keywords: Adolescent; Child, Preschool; Exome; Female; Genome-Wide Association Study; Humans; Hypopituitarism; Mutation; Pituitary Gland; Receptors, G-Protein-Coupled

Whole-exome sequencing identifies novel homozygous mutation in NPAS2 in family with nonobstructive azoospermia. - Ramasamy, Ranjith; Bakırcıoğlu, M Emre; Cengiz, Cenk; Karaca, Ender; Scovell, Jason; Jhangiani, Shalini N; Akdemir, Zeynep C; Bainbridge, Matthew; Yu, Yao; Huff, Chad; Gibbs, Richard A; Lupski, James R; et al. (Fertil Steril, 2015)
OBJECTIVE: To investigate the genetic cause of nonobstructive azoospermia (NOA) in a consanguineous Turkish family through homozygosity mapping followed by targeted exon/whole-exome sequencing to identify genetic variations. DESIGN: Whole-exome sequencing (WES). SETTING: Research laboratory. PATIENT(S): Two siblings in a consanguineous family with NOA. INTERVENTION(S): Validating all variants passing filter criteria with Sanger sequencing to confirm familial segregation and absence in the control population. MAIN OUTCOME MEASURE(S): Discovery of a mutation that could potentially cause NOA. RESULT(S): A novel nonsynonymous mutation in the neuronal PAS-2 domain (NPAS2) was identified in a consanguineous family from Turkey. This mutation in exon 14 (chr2: 101592000 C>G) of NPAS2 is likely a disease-causing mutation as it is predicted to be damaging, it is a novel variant, and it segregates with the disease. Family segregation of the variants showed the presence of the homozygous mutation in the three brothers with NOA and a heterozygous mutation in the mother as well as one brother and one sister who were both fertile. The mutation is not found in the single-nucleotide polymorphism database, the 1000 Genomes Project, the Baylor College of Medicine cohort of 500 Turkish patients (not a population-specific polymorphism), or the matching 50 fertile controls. CONCLUSION(S): With the use of WES we identified a novel homozygous mutation in NPAS2 as a likely disease-causing variant in a Turkish family diagnosed with NOA. Our data reinforce the clinical role of WES in the molecular diagnosis of highly heterogeneous genetic diseases for which conventional genetic approaches have previously failed to find a molecular diagnosis.
Keywords: Adult; Azoospermia; Base Sequence; Basic Helix-Loop-Helix Transcription Factors; Exome; Homozygote; Humans; Male; Molecular Sequence Data; Mutation; Nerve Tissue Proteins; Pedigree

X-linked acrogigantism syndrome: clinical profile and therapeutic responses. - Beckers, Albert; Lodish, Maya Beth; Trivellin, Giampaolo; Rostomyan, Liliya; Lee, Misu; Faucz, Fabio R; Yuan, Bo; Choong, Catherine S; Caberg, Jean-Hubert; Verrua, Elisa; Naves, Luciana Ansaneli; Cheetham, Tim D; et al. (Endocr Relat Cancer, 2015)
X-linked acrogigantism (X-LAG) is a new syndrome of pituitary gigantism, caused by microduplications on chromosome Xq26.3, encompassing the gene GPR101, which is highly upregulated in pituitary tumors. We conducted this study to explore the clinical, radiological, and hormonal phenotype and responses to therapy in patients with X-LAG syndrome. The study included 18 patients (13 sporadic) with X-LAG and microduplication of chromosome Xq26.3. All sporadic cases had unique duplications and the inheritance pattern in two families was dominant, with all Xq26.3 duplication carriers being affected. Patients began to grow rapidly as early as 2-3 months of age (median 12 months). At diagnosis (median delay 27 months), patients had a median height and weight standard deviation scores (SDS) of >+3.9 SDS. Apart from the increased overall body size, the children had acromegalic symptoms including acral enlargement and facial coarsening. More than a third of cases had increased appetite. Patients had marked hypersecretion of GH/IGF1 and usually prolactin, due to a pituitary macroadenoma or hyperplasia. Primary neurosurgical control was achieved with extensive anterior pituitary resection, but postoperative hypopituitarism was frequent. Control with somatostatin analogs was not readily achieved despite moderate to high levels of expression of somatostatin receptor subtype-2 in tumor tissue. Postoperative use of adjuvant pegvisomant resulted in control of IGF1 in all five cases where it was employed. X-LAG is a new infant-onset gigantism syndrome that has a severe clinical phenotype leading to challenging disease management.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Chromosomes, Human, X; Female; Gigantism; Humans; Infant; Male; Pituitary Neoplasms; Young Adult

γ-Secretase Mutation in an African American Family With Hidradenitis Suppurativa. - Chen, Sean; Mattei, Peter; You, Jing; Sobreira, Nara L; Hinds, Ginette A (JAMA Dermatol, 2015)
Keywords: Adolescent; Adult; African Americans; Amyloid Precursor Protein Secretases; Exome; Female; Hidradenitis Suppurativa; Humans; Membrane Glycoproteins; Middle Aged; Mutation; Sequence Analysis, DNA; Young Adult

Adenylate cyclase 1 (ADCY1) mutations cause recessive hearing impairment in humans and defects in hair cell function and hearing in zebrafish. - Santos-Cortez, Regie Lyn P; Lee, Kwanghyuk; Giese, Arnaud P; Ansar, Muhammad; Amin-ud-Din, Muhammad; Rehn, Kira; Wang, Xin; Aziz, Abdul; Chiu, Ilene; Hussain Ali, Raja; Smith, Joshua D; Shendure, Jay; et al. (Hum Mol Genet, 2014)
Cyclic AMP (cAMP) production, which is important for mechanotransduction within the inner ear, is catalyzed by adenylate cyclases (AC). However, knowledge of the role of ACs in hearing is limited. Previously, a novel autosomal recessive non-syndromic hearing impairment locus DFNB44 was mapped to chromosome 7p14.1-q11.22 in a consanguineous family from Pakistan. Through whole-exome sequencing of DNA samples from hearing-impaired family members, a nonsense mutation c.3112C>T (p.Arg1038*) within adenylate cyclase 1 (ADCY1) was identified. This stop-gained mutation segregated with hearing impairment within the family and was not identified in ethnically matched controls or within variant databases. This mutation is predicted to cause the loss of 82 amino acids from the carboxyl tail, including highly conserved residues within the catalytic domain, plus a calmodulin-stimulation defect, both of which are expected to decrease enzymatic efficiency. Individuals who are homozygous for this mutation had symmetric, mild-to-moderate mixed hearing impairment. Zebrafish adcy1b morphants had no FM1-43 dye uptake and lacked startle response, indicating hair cell dysfunction and gross hearing impairment. In the mouse, Adcy1 expression was observed throughout inner ear development and maturation. ADCY1 was localized to the cytoplasm of supporting cells and hair cells of the cochlea and vestibule and also to cochlear hair cell nuclei and stereocilia. Ex vivo studies in COS-7 cells suggest that the carboxyl tail of ADCY1 is essential for localization to actin-based microvilli. These results demonstrate that ADCY1 has an evolutionarily conserved role in hearing and that cAMP signaling is important to hair cell function within the inner ear.
Keywords: Adenylyl Cyclases; Animals; Cercopithecus aethiops; Codon, Nonsense; COS Cells; Cyclic AMP; Cytoplasm; Ear, Inner; Female; Hair Cells, Auditory; Hearing Loss; Humans; Labyrinth Supporting Cells; Male; Mice; Zebrafish

The Alu-rich genomic architecture of SPAST predisposes to diverse and functionally distinct disease-associated CNV alleles. - Boone, Philip M; Yuan, Bo; Campbell, Ian M; Scull, Jennifer C; Withers, Marjorie A; Baggett, Brett C; Beck, Christine R; Shaw, Christine J; Stankiewicz, Pawel; Moretti, Paolo; Goodwin, Wendy E; Hein, Nichole; et al. (Am J Hum Genet, 2014)
Intragenic copy-number variants (CNVs) contribute to the allelic spectrum of both Mendelian and complex disorders. Although pathogenic deletions and duplications in SPAST (mutations in which cause autosomal-dominant spastic paraplegia 4 [SPG4]) have been described, their origins and molecular consequences remain obscure. We mapped breakpoint junctions of 54 SPAST CNVs at nucleotide resolution. Diverse combinations of exons are deleted or duplicated, highlighting the importance of particular exons for spastin function. Of the 54 CNVs, 38 (70%) appear to be mediated by an Alu-based mechanism, suggesting that the Alu-rich genomic architecture of SPAST renders this locus susceptible to various genome rearrangements. Analysis of breakpoint Alus further informs a model of Alu-mediated CNV formation characterized by small CNV size and potential involvement of mechanisms other than homologous recombination. Twelve deletions (22%) overlap part of SPAST and a portion of a nearby, directly oriented gene, predicting novel chimeric genes in these subjects' genomes. cDNA from a subject with a SPAST final exon deletion contained multiple SPAST:SLC30A6 fusion transcripts, indicating that SPAST CNVs can have transcriptional effects beyond the gene itself. SLC30A6 has been implicated in Alzheimer disease, so these fusion gene data could explain a report of spastic paraplegia and dementia cosegregating in a family with deletion of the final exon of SPAST. Our findings provide evidence that the Alu genomic architecture of SPAST predisposes to diverse CNV alleles with distinct transcriptional--and possibly phenotypic--consequences. Moreover, we provide further mechanistic insights into Alu-mediated copy-number change that are extendable to other loci.
Keywords: Adenosine Triphosphatases; Alu Elements; Base Sequence; Cation Transport Proteins; Cell Line, Transformed; DNA Copy Number Variations; Genotype; Humans; Protein Isoforms; Recombinant Fusion Proteins; Sequence Analysis, DNA; Sequence Deletion; Spastic Paraplegia, Hereditary; Spastin

Attitudes of genetics professionals toward the return of incidental results from exome and whole-genome sequencing. - Yu, Joon-Ho; Harrell, Tanya M; Jamal, Seema M; Tabor, Holly K; Bamshad, Michael J (Am J Hum Genet, 2014)
Professional recommendations for the return of results from exome and whole-genome sequencing (ES/WGS) have been controversial. The lack of clear guidance about whether and, if so, how to return ES/WGS incidental results limits the extent to which individuals and families might benefit from ES/WGS. The perspectives of genetics professionals, particularly those at the forefront of using ES/WGS in clinics, are largely unknown. Data on stakeholder perspectives could help clarify how to weigh expert positions and recommendations. We conducted an online survey of 9,857 genetics professionals to learn their attitudes on the return of incidental results from ES/WGS and the recent American College of Medical Genetic and Genomics Recommendations for Reporting of Incidental Findings in Clinical Exome and Genome Sequencing. Of the 847 respondents, 760 completed the survey. The overwhelming majority of respondents thought that incidental ES/WGS results should be offered to adult patients (85%), healthy adults (75%), and the parents of a child with a medical condition (74%). The majority thought that incidental results about adult-onset conditions (62%) and carrier status (62%) should be offered to the parents of a child with a medical condition. About half thought that offered results should not be limited to those deemed clinically actionable. The vast majority (81%) thought that individual preferences should guide return. Genetics professionals' perspectives on the return of ES/WGS results differed substantially from current recommendations, underscoring the need to establish clear purpose for recommendations on the return of incidental ES/WGS results as professional societies grapple with developing and updating recommendations.
Keywords: Adult; Attitude of Health Personnel; Child; Exome; Genetics, Medical; Genome, Human; Humans; Incidental Findings; Workforce

Attitudes of non-African American focus group participants toward return of results from exome and whole genome sequencing. - Yu, Joon-Ho; Crouch, Julia; Jamal, Seema M; Bamshad, Michael J; Tabor, Holly K (Am J Med Genet A, 2014)
Exome sequencing and whole genome sequencing (ES/WGS) present individuals with the opportunity to benefit from a broad scope of genetic results of clinical and personal utility. Yet, it is unclear which genetic results people want to receive (i.e., what type of genetic information they want to learn about themselves) or conversely not receive, and how they want to receive or manage results over time. Very little is known about whether and how attitudes toward receiving individual results from ES/WGS vary among racial/ethnic populations. We conducted 13 focus groups with a racially and ethnically diverse parent population (n = 76) to investigate attitudes toward return of individual results from WGS. We report on our findings for non-African American (non-AA) participants. Non-AA participants were primarily interested in genetic results on which they could act or "do something about." They defined "actionability" broadly to include individual medical treatment and disease prevention. The ability to plan for the future was both a motivation for and an expected benefit of receiving results. Their concerns focused on the meaning of results, specifically the potential inaccuracy and uncertainty of results. Non-AA participants expected healthcare providers to be involved in results management by helping them interpret results in the context of their own health and by providing counseling support. We compare and contrast these themes with those we previously reported from our analysis of African American (AA) perspectives to highlight the importance of varying preferences for results, characterize the central role of temporal orientation in framing expectations about the possibility of receiving ES/WGS results, and identify potential avenues by which genomic healthcare disparities may be inadvertently perpetuated.
Keywords: Adult; African Americans; Aged; Attitude to Health; Exome; Female; Focus Groups; Genome, Human; Humans; Male; Middle Aged; Sequence Analysis, DNA

Biallelic truncating mutations in FMN2, encoding the actin-regulatory protein Formin 2, cause nonsyndromic autosomal-recessive intellectual disability. - Law, Rosalind; Dixon-Salazar, Tracy; Jerber, Julie; Cai, Na; Abbasi, Ansar A; Zaki, Maha S; Mittal, Kirti; Gabriel, Stacey B; Rafiq, Muhammad Arshad; Khan, Valeed; Nguyen, Maria; Ali, Ghazanfar; et al. (Am J Hum Genet, 2014)
Dendritic spines represent the major site of neuronal activity in the brain; they serve as the receiving point for neurotransmitters and undergo rapid activity-dependent morphological changes that correlate with learning and memory. Using a combination of homozygosity mapping and next-generation sequencing in two consanguineous families affected by nonsyndromic autosomal-recessive intellectual disability, we identified truncating mutations in formin 2 (FMN2), encoding a protein that belongs to the formin family of actin cytoskeleton nucleation factors and is highly expressed in the maturing brain. We found that FMN2 localizes to punctae along dendrites and that germline inactivation of mouse Fmn2 resulted in animals with decreased spine density; such mice were previously demonstrated to have a conditioned fear-learning defect. Furthermore, patient neural cells derived from induced pluripotent stem cells showed correlated decreased synaptic density. Thus, FMN2 mutations link intellectual disability either directly or indirectly to the regulation of actin-mediated synaptic spine density.
Keywords: Adolescent; Adult; Base Sequence; Chromosome Disorders; Cohort Studies; Consanguinity; Egypt; Exome; Female; Genes, Recessive; Genetic Linkage; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Intellectual Disability; Male; Microfilament Proteins; Molecular Sequence Data; Nuclear Proteins; Pakistan; Pedigree; Sequence Analysis, DNA; Sequence Deletion

Brain malformations associated with Knobloch syndrome--review of literature, expanding clinical spectrum, and identification of novel mutations. - Çağlayan, Ahmet Okay; Baranoski, Jacob F; Aktar, Fesih; Han, Wengi; Tuysuz, Beyhan; Guzel, Aslan; Guclu, Bulent; Kaymakçalan, Hande; Aktekin, Berrin; Akgümüş, Gözde Tuğce; Murray, Phillip B; Erson-Omay, Emine Z; et al. (Pediatr Neurol, 2014)
BACKGROUND: Knobloch syndrome is a rare, autosomal recessive, developmental disorder characterized by stereotyped ocular abnormalities with or without occipital skull deformities (encephalocele, bone defects, and cutis aplasia). Although there is clear heterogeneity in clinical presentation, central nervous system malformations, aside from the characteristic encephalocele, have not typically been considered a component of the disease phenotype. METHODS: Four patients originally presented for genetic evaluation of symptomatic structural brain malformations. Whole-genome genotyping, whole-exome sequencing, and confirmatory Sanger sequencing were performed. Using immunohistochemical analysis, we investigated the protein expression pattern of COL18A1 in the mid-fetal and adult human cerebral cortex and then analyzed the spatial and temporal changes in the expression pattern of COL18A1 during human cortical development using the Human Brain Transcriptome database. RESULTS: We identified two novel homozygous deleterious frame-shift mutations in the COL18A1 gene. On further investigation of these patients and their families, we found that many exhibited certain characteristics of Knobloch syndrome, including pronounced ocular defects. Our data strongly support an important role for COL18A1 in brain development, and this report contributes to an enhanced characterization of the brain malformations that can result from deficiencies of collagen XVIII. CONCLUSIONS: This case series highlights the diagnostic power and clinical utility of whole-exome sequencing technology-allowing clinicians and physician scientists to better understand the pathophysiology and presentations of rare diseases. We suggest that patients who are clinically diagnosed with Knobloch syndrome and/or found to have COL18A1 mutations via genetic screening should be investigated for potential structural brain abnormalities even in the absence of an encephalocele.
Keywords: Adolescent; Adult; Cerebral Cortex; Collagen Type XVIII; Consanguinity; Encephalocele; Exome; Female; Fetus; Humans; Male; Mutation; Retinal Degeneration; Retinal Detachment; Young Adult

Clinical utility of whole-exome sequencing in rare diseases: Galactosialidosis. - Prada, Carlos E; Gonzaga-Jauregui, Claudia; Tannenbaum, Rebecca; Penney, Samantha; Lupski, James R; Hopkin, Robert J; Sutton, V Reid (Eur J Med Genet, 2014)
Rare genetic disorders can go undiagnosed for years as the entire spectrum of phenotypic variation is not well characterized given the reduced number of patients reported in the literature and the low frequency at which these occur. Moreover, the current paradigm for clinical diagnostics defines disease diagnosis by a specified spectrum of phenotypic findings; when such parameters are either missing, or other findings not usually observed are seen, the phenotype driven approach to diagnosis may result in a specific etiological diagnosis not even being considered within the differential diagnosis. The novel implementation of genomic sequencing approaches to investigate rare genetic disorders is allowing not only the discovery of new genes, but also the phenotypic expansion of known Mendelian genetic disorders. Here we report the detailed clinical assessment of a patient with a rare genetic disorder with undefined molecular diagnosis. We applied whole-exome sequencing to this patient and unaffected parents in order to identify the molecular cause of her disorder. We identified compound heterozygous mutations in the CTSA gene, responsible for causing galactosialidosis; the molecular diagnosis was further confirmed by biochemical studies. This report expands on the clinical spectrum of this rare lysosomal disorder and exemplifies how genomic approaches are further elucidating the characterization and understanding of genetic diseases.
Keywords: Adult; Cathepsin A; Exome; Female; Humans; Lysosomal Storage Diseases; Mutation; Rare Diseases; Sequence Analysis, DNA; Young Adult

CLP1 founder mutation links tRNA splicing and maturation to cerebellar development and neurodegeneration. - Schaffer, Ashleigh E; Eggens, Veerle R C; Çağlayan, Ahmet Okay; Reuter, Miriam S; Scott, Eric; Coufal, Nicole G; Silhavy, Jennifer L; Xue, Yuanchao; Kayserili, Hülya; Yasuno, Katsuhito; Rosti, Rasim Ozgur; Abdellateef, Mostafa; et al. (Cell, 2014)
Neurodegenerative diseases can occur so early as to affect neurodevelopment. From a cohort of more than 2,000 consanguineous families with childhood neurological disease, we identified a founder mutation in four independent pedigrees in cleavage and polyadenylation factor I subunit 1 (CLP1). CLP1 is a multifunctional kinase implicated in tRNA, mRNA, and siRNA maturation. Kinase activity of the CLP1 mutant protein was defective, and the tRNA endonuclease complex (TSEN) was destabilized, resulting in impaired pre-tRNA cleavage. Germline clp1 null zebrafish showed cerebellar neurodegeneration that was rescued by wild-type, but not mutant, human CLP1 expression. Patient-derived induced neurons displayed both depletion of mature tRNAs and accumulation of unspliced pre-tRNAs. Transfection of partially processed tRNA fragments into patient cells exacerbated an oxidative stress-induced reduction in cell survival. Our data link tRNA maturation to neuronal development and neurodegeneration through defective CLP1 function in humans.
Keywords: Animals; Brain; Cerebellum; Cleavage And Polyadenylation Specificity Factor; Female; Humans; Male; Mice; Models, Molecular; Neurodegenerative Diseases; Nuclear Proteins; Pedigree; Phosphotransferases; RNA Splicing; RNA, Transfer; Saccharomyces cerevisiae; Transcription Factors; Zebrafish; Zebrafish Proteins

Compound heterozygous CORO1A mutations in siblings with a mucocutaneous-immunodeficiency syndrome of epidermodysplasia verruciformis-HPV, molluscum contagiosum and granulomatous tuberculoid leprosy. - Stray-Pedersen, Asbjorg; Jouanguy, Emmanuelle; Crequer, Amandine; Bertuch, Alison A; Brown, Betty S; Jhangiani, Shalini N; Muzny, Donna M; Gambin, Tomasz; Sorte, Hanne; Sasa, Ghadir; Metry, Denise; Campbell, Judith; et al. (J Clin Immunol, 2014)
PURPOSE: Coronin-1A deficiency is a recently recognized autosomal recessive primary immunodeficiency caused by mutations in CORO1A (OMIM 605000) that results in T-cell lymphopenia and is classified as T(-)B(+)NK(+)severe combined immunodeficiency (SCID). Only two other CORO1A-kindred are known to date, thus the defining characteristics are not well delineated. We identified a unique CORO1A-kindred. METHODS: We captured a 10-year analysis of the immune-clinical phenotypes in two affected siblings from disease debut of age 7 years. Target-specific genetic studies were pursued but unrevealing. Telomere lengths were also assessed. Whole exome sequencing (WES) uncovered the molecular diagnosis and Western blot validated findings. RESULTS: We found the compound heterozygous CORO1A variants: c.248_249delCT (p.P83RfsX10) and a novel mutation c.1077delC (p.Q360RfsX44) (NM_007074.3) in two affected non-consanguineous siblings that manifested as absent CD4CD45RA(+) (naïve) T and memory B cells, low NK cells and abnormally increased double-negative (DN) ϒδ T-cells. Distinguishing characteristics were late clinical debut with an unusual mucocutaneous syndrome of epidermodysplasia verruciformis-human papilloma virus (EV-HPV), molluscum contagiosum and oral-cutaneous herpetic ulcers; the older female sibling also had a disfiguring granulomatous tuberculoid leprosy. Both had bilateral bronchiectasis and the female died of EBV+ lymphomas at age 16 years. The younger surviving male, without malignancy, had reproducibly very short telomere lengths, not before appreciated in CORO1A mutations. CONCLUSION: We reveal the third CORO1A-mutated kindred, with the immune phenotype of abnormal naïve CD4 and DN T-cells and newfound characteristics of a late/hypomorphic-like SCID of an EV-HPV mucocutaneous syndrome with also B and NK defects and shortened telomeres. Our findings contribute to the elucidation of the CORO1A-SCID-CID spectrum.
Keywords: Adolescent; B-Lymphocytes; CD4-Positive T-Lymphocytes; Child; DNA Mutational Analysis; Epidermodysplasia Verruciformis; Female; Genetic Predisposition to Disease; Granuloma; Heterozygote; Humans; Immunologic Memory; Killer Cells, Natural; Leprosy, Tuberculoid; Male; Microfilament Proteins; Molluscum Contagiosum; Mucous Membrane; Mutation; Papillomavirus Infections; Polymorphism, Genetic; Severe Combined Immunodeficiency; Siblings; Skin; Telomere Shortening

Cytogenomic delineation and clinical follow-up of two siblings with an 8.5 Mb 6q24.2-q25.2 deletion inherited from a paternal insertion. - Meloni, Vera Ayres; Guilherme, Roberta Santos; Oliveira, Mariana Moyses; Migliavacca, Michele; Takeno, Sylvia Satomi; Sobreira, Nara Lygia Macena; de Fatima Faria Soares, Maria; de Mello, Claudia Berlim; Melaragno, Maria Isabel (Am J Med Genet A, 2014)
The chromosomal segment 6q24-q25 comprises a contiguous gene microdeletion syndrome characterized by intrauterine growth retardation, growth delay, intellectual disability, cardiac anomalies, and a dysmorphic facial phenotype. We describe here a 10-year follow-up with detailed clinical, neuropsychological, and cytomolecular data of two siblings, male and female, who presented with developmental delay, microcephaly, short stature, characteristic facial dysmorphisms, multiple organ anomalies, and intellectual disability. Microarray analysis showed an 8.5 Mb 6q24.2-q25.2 interstitial deletion. Fluorescence in situ hybridization analyses confirmed the deletions and identified an insertion of 6q into 8q13 in their father, resulting in a high recurrence risk. This is the first report in sibs with distinct neuropsychological involvement, one of them with stenosis of the descending branch of the aorta.
Keywords: Adolescent; Base Pairing; Child; Child, Preschool; Chromosome Deletion; Chromosomes, Human, Pair 6; Cytogenetic Analysis; Fathers; Female; Follow-Up Studies; Humans; Infant, Newborn; Inheritance Patterns; Male; Mutagenesis, Insertional; Siblings

De novo truncating mutations in AHDC1 in individuals with syndromic expressive language delay, hypotonia, and sleep apnea. - Xia, Fan; Bainbridge, Matthew N; Tan, Tiong Yang; Wangler, Michael F; Scheuerle, Angela E; Zackai, Elaine H; Harr, Margaret H; Sutton, V Reid; Nalam, Roopa L; Zhu, Wenmiao; Nash, Margot; Ryan, Monique M; et al. (Am J Hum Genet, 2014)
Clinical whole-exome sequencing (WES) for identification of mutations leading to Mendelian disease has been offered to the medical community since 2011. Clinically undiagnosed neurological disorders are the most frequent basis for test referral, and currently, approximately 25% of such cases are diagnosed at the molecular level. To date, there are approximately 4,000 "known" disease-associated loci, and many are associated with striking dysmorphic features, making genotype-phenotype correlations relatively straightforward. A significant fraction of cases, however, lack characteristic dysmorphism or clinical pathognomonic traits and are dependent upon molecular tests for definitive diagnoses. Further, many molecular diagnoses are guided by recent gene-disease association discoveries. Hence, there is a critical interplay between clinical testing and research leading to gene-disease association discovery. Here, we describe four probands, all of whom presented with hypotonia, intellectual disability, global developmental delay, and mildly dysmorphic facial features. Three of the four also had sleep apnea. Each was a simplex case without a remarkable family history. Using WES, we identified AHDC1 de novo truncating mutations that most likely cause this genetic syndrome.
Keywords: Child; Child, Preschool; DNA-Binding Proteins; Exome; Female; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Muscle Hypotonia; Mutation; Sleep Apnea Syndromes; Syndrome

Diagnosis of ALG12-CDG by exome sequencing in a case of severe skeletal dysplasia. - Murali, Chaya; Lu, James T; Jain, Mahim; Liu, David S; Lachman, Ralph; Gibbs, Richard A; Lee, Brendan H; Cohn, Daniel; Campeau, Philippe M (Mol Genet Metab Rep, 2014)
Congenital Disorder of Glycosylation type Ig (ALG12-CDG) is part of a group of autosomal recessive conditions caused by deficiency of proteins involved in the assembly of dolichol-oligosaccharides used for protein N-glycosylation. In ALG12-CDG, the enzyme affected is encoded by the gene. Affected individuals present clinically with neurodevelopmental delay, growth retardation, immune deficiency, male genital hypoplasia, and cardiomyopathy. A total of six individuals have been reported in the literature. Here, we present an infant with rhizomelic short stature, talipes equinovarus, platyspondyly, and joint dislocations. The infant had marked underossification of the pubic bones. Exome sequencing was performed and two deletions, each resulting in frameshifts, were found in . A review of the literature revealed two infants with ALG12-CDG and a severe skeletal dysplasia, including under-ossification of cervical vertebrae, pubic bones, and knees; in addition to talipes equinovarus and rhizomelic short stature. The phenotype of the individual we describe resembles pseudodiastrophic dysplasia and we discuss similarities and differences between ALG12-CDG and pseudodiastrophic dysplasia. The differential diagnosis in selected undiagnosed skeletal dysplasias should include CDGs.

Diamond-Blackfan anemia with mandibulofacial dystostosis is heterogeneous, including the novel DBA genes TSR2 and RPS28. - Gripp, Karen W; Curry, Cynthia; Olney, Ann Haskins; Sandoval, Claudio; Fisher, Jamie; Chong, Jessica Xiao-Ling; Pilchman, Lisa; Sahraoui, Rebecca; Stabley, Deborah L; Sol-Church, Katia (Am J Med Genet A, 2014)
Patients with physical findings suggestive of Treacher Collins syndrome (TCS) or mandibulofacial dysostosis (MFD) and macrocytic anemia diagnostic of Diamond-Blackfan anemia (DBA) have been reported. Disease-causing genes have been identified for TCS and other MFDs. Mutations in several ribosomal protein genes and the transcription factor GATA1 result in DBA. However, no disease-causing mutation had been identified in the reported patients with the combination of TCS/MFD and DBA phenotype, and we hypothesized that pathogenic mutations in a single gene could be identified using whole exome analysis. We studied probands from six unrelated families. Combining exome analysis and Sanger sequencing, we identified likely pathogenic mutations in 5/6 families. Two mutations in unrelated families were seen in RPS26, the known DBA10 gene. One variant was predicted to affect mRNA splicing, and the other to lead to protein truncation. In another family a likely pathogenic X-linked mutation affecting a highly conserved residue was found in TSR2, which encodes a direct binding partner of RPS26. De novo mutations affecting the RPS28 start codon were found in two unrelated probands, identifying RPS28 as a novel disease gene. We conclude that the phenotype combining features of TCS with DBA is genetically heterogeneous. Each of the pathogenic variants identified is predicted to impede ribosome biogenesis, which in turn could result in altered cell growth and proliferation, causing abnormal embryologic development, defective erythropoiesis and reduced growth. The phenotype combining TCS/MFD and DBA is highly variable, overlaps with DBA and lies within the phenotypic spectrum of ribosomopathies. © 2014 Wiley Periodicals, Inc.
Keywords: Adult; Anemia, Diamond-Blackfan; Apoptosis Regulatory Proteins; Child, Preschool; Exome; Family; Female; Genetic Heterogeneity; Humans; Infant; Infant, Newborn; Male; Mandibulofacial Dysostosis; Pedigree; Phenotype; Pregnancy; Ribosomal Proteins; Young Adult

DIAMUND: direct comparison of genomes to detect mutations. - Salzberg, Steven L; Pertea, Mihaela; Fahrner, Jill A; Sobreira, Nara (Hum Mutat, 2014)
DNA sequencing has become a powerful method to discover the genetic basis of disease. Standard, widely used protocols for analysis usually begin by comparing each individual to the human reference genome. When applied to a set of related individuals, this approach reveals millions of differences, most of which are shared among the individuals and unrelated to the disease being investigated. We have developed a novel algorithm for variant detection, one that compares DNA sequences directly to one another, without aligning them to the reference genome. When used to find de novo mutations in exome sequences from family trios, or to compare normal and diseased samples from the same individual, the new method, direct alignment for mutation discovery (DIAMUND), produces a dramatically smaller list of candidate mutations than previous methods, without losing sensitivity to detect the true cause of a genetic disease. We demonstrate our results on several example cases, including two family trios in which it correctly found the disease-causing variant while excluding thousands of harmless variants that standard methods had identified.
Keywords: Algorithms; Computational Biology; Exome; Genetic Loci; Genetic Variation; Genome, Human; Humans; Mutation; Sequence Alignment; Sequence Analysis, DNA; Software

Dosage changes of a segment at 17p13.1 lead to intellectual disability and microcephaly as a result of complex genetic interaction of multiple genes. - Carvalho, Claudia M B; Vasanth, Shivakumar; Shinawi, Marwan; Russell, Chad; Ramocki, Melissa B; Brown, Chester W; Graakjaer, Jesper; Skytte, Anne-Bine; Vianna-Morgante, Angela M; Krepischi, Ana C V; Patel, Gayle S; Immken, LaDonna; et al. (Am J Hum Genet, 2014)
The 17p13.1 microdeletion syndrome is a recently described genomic disorder with a core clinical phenotype of intellectual disability, poor to absent speech, dysmorphic features, and a constellation of more variable clinical features, most prominently microcephaly. We identified five subjects with copy-number variants (CNVs) on 17p13.1 for whom we performed detailed clinical and molecular studies. Breakpoint mapping and retrospective analysis of published cases refined the smallest region of overlap (SRO) for microcephaly to a genomic interval containing nine genes. Dissection of this phenotype in zebrafish embryos revealed a complex genetic architecture: dosage perturbation of four genes (ASGR1, ACADVL, DVL2, and GABARAP) impeded neurodevelopment and decreased dosage of the same loci caused a reduced mitotic index in vitro. Moreover, epistatic analyses in vivo showed that dosage perturbations of discrete gene pairings induce microcephaly. Taken together, these studies support a model in which concomitant dosage perturbation of multiple genes within the CNV drive the microcephaly and possibly other neurodevelopmental phenotypes associated with rearrangements in the 17p13.1 SRO.
Keywords: Abnormalities, Multiple; Acyl-CoA Dehydrogenase, Long-Chain; Adaptor Proteins, Signal Transducing; Animals; Asialoglycoprotein Receptor; Base Sequence; Cell Line; Chromosome Breakpoints; Chromosome Deletion; Chromosomes, Human, Pair 17; Dishevelled Proteins; Flow Cytometry; Gene Dosage; Humans; Immunohistochemistry; Intellectual Disability; Microcephaly; Microtubule-Associated Proteins; Molecular Sequence Data; Phosphoproteins; Retrospective Studies; Sequence Analysis, DNA; Smith-Magenis Syndrome; Syndrome; Zebrafish

A drosophila genetic resource of mutants to study mechanisms underlying human genetic diseases. - Yamamoto, Shinya; Jaiswal, Manish; Charng, Wu-Lin; Gambin, Tomasz; Karaca, Ender; Mirzaa, Ghayda; Wiszniewski, Wojciech; Sandoval, Hector; Haelterman, Nele A; Xiong, Bo; Zhang, Ke; Bayat, Vafa; et al. (Cell, 2014)
Invertebrate model systems are powerful tools for studying human disease owing to their genetic tractability and ease of screening. We conducted a mosaic genetic screen of lethal mutations on the Drosophila X chromosome to identify genes required for the development, function, and maintenance of the nervous system. We identified 165 genes, most of whose function has not been studied in vivo. In parallel, we investigated rare variant alleles in 1,929 human exomes from families with unsolved Mendelian disease. Genes that are essential in flies and have multiple human homologs were found to be likely to be associated with human diseases. Merging the human data sets with the fly genes allowed us to identify disease-associated mutations in six families and to provide insights into microcephaly associated with brain dysgenesis. This bidirectional synergism between fly genetics and human genomics facilitates the functional annotation of evolutionarily conserved genes involved in human health.
Keywords: Animals; Disease; Disease Models, Animal; Drosophila melanogaster; Genetic Testing; Humans; Inheritance Patterns; RNA Interference; X Chromosome

Exome sequencing identifies a recurrent de novo ZSWIM6 mutation associated with acromelic frontonasal dysostosis. - Smith, Joshua D; Hing, Anne V; Clarke, Christine M; Johnson, Nathan M; Perez, Francisco A; Park, Sarah S; Horst, Jeremy A; Mecham, Brig; Maves, Lisa; Nickerson, Deborah A; Cunningham, Michael L (Am J Hum Genet, 2014)
Acromelic frontonasal dysostosis (AFND) is a rare disorder characterized by distinct craniofacial, brain, and limb malformations, including frontonasal dysplasia, interhemispheric lipoma, agenesis of the corpus callosum, tibial hemimelia, preaxial polydactyly of the feet, and intellectual disability. Exome sequencing of one trio and two unrelated probands revealed the same heterozygous variant (c.3487C>T [p. Arg1163Trp]) in a highly conserved protein domain of ZSWIM6; this variant has not been seen in the 1000 Genomes data, dbSNP, or the Exome Sequencing Project. Sanger validation of the three trios confirmed that the variant was de novo and was also present in a fourth isolated proband. In situ hybridization of early zebrafish embryos at 24 hr postfertilization (hpf) demonstrated telencephalic expression of zswim6 and onset of midbrain, hindbrain, and retinal expression at 48 hpf. Immunohistochemistry of later-stage mouse embryos demonstrated tissue-specific expression in the derivatives of all three germ layers. qRT-PCR expression analysis of osteoblast and fibroblast cell lines available from two probands was suggestive of Hedgehog pathway activation, indicating that the ZSWIM6 mutation associated with AFND may lead to the craniofacial, brain and limb malformations through the disruption of Hedgehog signaling.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Craniofacial Abnormalities; DNA Mutational Analysis; DNA-Binding Proteins; Exome; Face; Hedgehog Proteins; Humans; Intellectual Disability; Limb Deformities, Congenital; Mandibulofacial Dysostosis; Mice; Molecular Sequence Data; Mutation; Protein Structure, Tertiary; Zebrafish; Zinc Fingers

Exome sequencing links corticospinal motor neuron disease to common neurodegenerative disorders. - Novarino, Gaia; Fenstermaker, Ali G; Zaki, Maha S; Hofree, Matan; Silhavy, Jennifer L; Heiberg, Andrew D; Abdellateef, Mostafa; Rosti, Basak; Scott, Eric; Mansour, Lobna; Masri, Amira; Kayserili, Hülya; et al. (Science, 2014)
Hereditary spastic paraplegias (HSPs) are neurodegenerative motor neuron diseases characterized by progressive age-dependent loss of corticospinal motor tract function. Although the genetic basis is partly understood, only a fraction of cases can receive a genetic diagnosis, and a global view of HSP is lacking. By using whole-exome sequencing in combination with network analysis, we identified 18 previously unknown putative HSP genes and validated nearly all of these genes functionally or genetically. The pathways highlighted by these mutations link HSP to cellular transport, nucleotide metabolism, and synapse and axon development. Network analysis revealed a host of further candidate genes, of which three were mutated in our cohort. Our analysis links HSP to other neurodegenerative disorders and can facilitate gene discovery and mechanistic understanding of disease.
Keywords: Animals; Axons; Biological Transport; Cohort Studies; Exome; Gene Regulatory Networks; Genetic Association Studies; Humans; Motor Neuron Disease; Mutation; Neurons; Nucleotides; Pyramidal Tracts; Sequence Analysis, DNA; Spastic Paraplegia, Hereditary; Synapses; Transcriptome; Zebrafish

Exonic duplication CNV of NDRG1 associated with autosomal-recessive HMSN-Lom/CMT4D. - Okamoto, Yuji; Goksungur, Meryem Tuba; Pehlivan, Davut; Beck, Christine R; Gonzaga-Jauregui, Claudia; Muzny, Donna M; Atik, Mehmed M; Carvalho, Claudia M B; Matur, Zeliha; Bayraktar, Serife; Boone, Philip M; Akyuz, Kaya; et al. (Genet Med, 2014)
PURPOSE: Copy-number variations as a mutational mechanism contribute significantly to human disease. Approximately one-half of the patients with Charcot-Marie-Tooth (CMT) disease have a 1.4 Mb duplication copy-number variation as the cause of their neuropathy. However, non-CMT1A neuropathy patients rarely have causative copy-number variations, and to date, autosomal-recessive disease has not been associated with copy-number variation as a mutational mechanism. METHODS: We performed Agilent 8 × 60 K array comparative genomic hybridization on DNA from 12 recessive Turkish families with CMT disease. Additional molecular studies were conducted to detect breakpoint junctions and to evaluate gene expression levels in a family in which we detected an intragenic duplication copy-number variation. RESULTS: We detected an ~6.25 kb homozygous intragenic duplication in NDRG1, a gene known to be causative for recessive HMSNL/CMT4D, in three individuals from a Turkish family with CMT neuropathy. Further studies showed that this intragenic copy-number variation resulted in a homozygous duplication of exons 6-8 that caused decreased mRNA expression of NDRG1. CONCLUSION: Exon-focused high-resolution array comparative genomic hybridization enables the detection of copy-number variation carrier states in recessive genes, particularly small copy-number variations encompassing or disrupting single genes. In families for whom a molecular diagnosis has not been elucidated by conventional clinical assays, an assessment for copy-number variations in known CMT genes might be considered.
Keywords: Adult; Base Sequence; Cell Cycle Proteins; Charcot-Marie-Tooth Disease; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Expression; Genes, Recessive; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation; Refsum Disease; Sequence Analysis, DNA; Turkey; Young Adult

Expanding the phenotypic spectrum of ARID1B-mediated disorders and identification of altered cell-cycle dynamics due to ARID1B haploinsufficiency. - Sim, Joe C H; White, Susan M; Fitzpatrick, Elizabeth; Wilson, Gabrielle R; Gillies, Greta; Pope, Kate; Mountford, Hayley S; Torring, Pernille M; McKee, Shane; Vulto-van Silfhout, Anneke T; Jhangiani, Shalini N; Muzny, Donna M; et al. (Orphanet J Rare Dis, 2014)
BACKGROUND: Mutations in genes encoding components of the Brahma-associated factor (BAF) chromatin remodeling complex have recently been shown to contribute to multiple syndromes characterised by developmental delay and intellectual disability. ARID1B mutations have been identified as the predominant cause of Coffin-Siris syndrome and have also been shown to be a frequent cause of nonsyndromic intellectual disability. Here, we investigate the molecular basis of a patient with an overlapping but distinctive phenotype of intellectual disability, plantar fat pads and facial dysmorphism. METHODS/RESULTS: High density microarray analysis of the patient demonstrated a heterozygous deletion at 6q25.3, which resulted in the loss of four genes including AT Rich Interactive Domain 1B (ARID1B). Subsequent quantitative real-time PCR analysis revealed ARID1B haploinsufficiency in the patient. Analysis of both patient-derived and ARID1B knockdown fibroblasts after serum starvation demonstrated delayed cell cycle re-entry associated with reduced cell number in the S1 phase. Based on the patient's distinctive phenotype, we ascertained four additional patients and identified heterozygous de novo ARID1B frameshift or nonsense mutations in all of them. CONCLUSIONS: This study broadens the spectrum of ARID1B associated phenotypes by describing a distinctive phenotype including plantar fat pads but lacking the hypertrichosis or fifth nail hypoplasia associated with Coffin-Siris syndrome. We present the first direct evidence in patient-derived cells that alterations in cell cycle contribute to the underlying pathogenesis of syndromes associated with ARID1B haploinsufficiency.
Keywords: Abnormalities, Multiple; Cell Cycle; Chromatin Assembly and Disassembly; DNA-Binding Proteins; Face; Female; Hand Deformities, Congenital; Haploinsufficiency; Humans; Intellectual Disability; Male; Micrognathism; Neck; Transcription Factors

A form of the metabolic syndrome associated with mutations in DYRK1B. - Keramati, Ali R; Fathzadeh, Mohsen; Go, Gwang-Woong; Singh, Rajvir; Choi, Murim; Faramarzi, Saeed; Mane, Shrikant; Kasaei, Mohammad; Sarajzadeh-Fard, Kazem; Hwa, John; Kidd, Kenneth K; Babaee Bigi, Mohammad A; et al. (N Engl J Med, 2014)
BACKGROUND: Genetic analysis has been successful in identifying causative mutations for individual cardiovascular risk factors. Success has been more limited in mapping susceptibility genes for clusters of cardiovascular risk traits, such as those in the metabolic syndrome. METHODS: We identified three large families with coinheritance of early-onset coronary artery disease, central obesity, hypertension, and diabetes. We used linkage analysis and whole-exome sequencing to identify the disease-causing gene. RESULTS: A founder mutation was identified in DYRK1B, substituting cysteine for arginine at position 102 in the highly conserved kinase-like domain. The mutation precisely cosegregated with the clinical syndrome in all the affected family members and was absent in unaffected family members and unrelated controls. Functional characterization of the disease gene revealed that nonmutant protein encoded by DYRK1B inhibits the SHH (sonic hedgehog) and Wnt signaling pathways and consequently enhances adipogenesis. Furthermore, DYRK1B promoted the expression of the key gluconeogenic enzyme glucose-6-phosphatase. The R102C allele showed gain-of-function activities by potentiating these effects. A second mutation, substituting proline for histidine 90, was found to cosegregate with a similar clinical syndrome in an ethnically distinct family. CONCLUSIONS: These findings indicate a role for DYRK1B in adipogenesis and glucose homeostasis and associate its altered function with an inherited form of the metabolic syndrome. (Funded by the National Institutes of Health.).
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Female; Founder Effect; Genetic Linkage; Genetic Predisposition to Disease; Glucose-6-Phosphatase; Humans; Hypertension; Male; Metabolic Syndrome; Mutation; Obesity, Abdominal; Pedigree; Protein-Serine-Threonine Kinases; Protein-Tyrosine Kinases

A general framework for estimating the relative pathogenicity of human genetic variants. - Kircher, Martin; Witten, Daniela M; Jain, Preti; O'Roak, Brian J; Cooper, Gregory M; Shendure, Jay (Nat Genet, 2014)
Current methods for annotating and interpreting human genetic variation tend to exploit a single information type (for example, conservation) and/or are restricted in scope (for example, to missense changes). Here we describe Combined Annotation-Dependent Depletion (CADD), a method for objectively integrating many diverse annotations into a single measure (C score) for each variant. We implement CADD as a support vector machine trained to differentiate 14.7 million high-frequency human-derived alleles from 14.7 million simulated variants. We precompute C scores for all 8.6 billion possible human single-nucleotide variants and enable scoring of short insertions-deletions. C scores correlate with allelic diversity, annotations of functionality, pathogenicity, disease severity, experimentally measured regulatory effects and complex trait associations, and they highly rank known pathogenic variants within individual genomes. The ability of CADD to prioritize functional, deleterious and pathogenic variants across many functional categories, effect sizes and genetic architectures is unmatched by any current single-annotation method.
Keywords: Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; INDEL Mutation; Models, Genetic; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Selection, Genetic; Support Vector Machine

The genetic basis of DOORS syndrome: an exome-sequencing study. - Campeau, Philippe M; Kasperaviciute, Dalia; Lu, James T; Burrage, Lindsay C; Kim, Choel; Hori, Mutsuki; Powell, Berkley R; Stewart, Fiona; Félix, Têmis Maria; van den Ende, Jenneke; Wisniewska, Marzena; Kayserili, Hülya; et al. (Lancet Neurol, 2014)
BACKGROUND: Deafness, onychodystrophy, osteodystrophy, mental retardation, and seizures (DOORS) syndrome is a rare autosomal recessive disorder of unknown cause. We aimed to identify the genetic basis of this syndrome by sequencing most coding exons in affected individuals. METHODS: Through a search of available case studies and communication with collaborators, we identified families that included at least one individual with at least three of the five main features of the DOORS syndrome: deafness, onychodystrophy, osteodystrophy, intellectual disability, and seizures. Participants were recruited from 26 centres in 17 countries. Families described in this study were enrolled between Dec 1, 2010, and March 1, 2013. Collaborating physicians enrolling participants obtained clinical information and DNA samples from the affected child and both parents if possible. We did whole-exome sequencing in affected individuals as they were enrolled, until we identified a candidate gene, and Sanger sequencing to confirm mutations. We did expression studies in human fibroblasts from one individual by real-time PCR and western blot analysis, and in mouse tissues by immunohistochemistry and real-time PCR. FINDINGS: 26 families were included in the study. We did exome sequencing in the first 17 enrolled families; we screened for TBC1D24 by Sanger sequencing in subsequent families. We identified TBC1D24 mutations in 11 individuals from nine families (by exome sequencing in seven families, and Sanger sequencing in two families). 18 families had individuals with all five main features of DOORS syndrome, and TBC1D24 mutations were identified in half of these families. The seizure types in individuals with TBC1D24 mutations included generalised tonic-clonic, complex partial, focal clonic, and infantile spasms. Of the 18 individuals with DOORS syndrome from 17 families without TBC1D24 mutations, eight did not have seizures and three did not have deafness. In expression studies, some mutations abrogated TBC1D24 mRNA stability. We also detected Tbc1d24 expression in mouse phalangeal chondrocytes and calvaria, which suggests a role of TBC1D24 in skeletogenesis. INTERPRETATION: Our findings suggest that mutations in TBC1D24 seem to be an important cause of DOORS syndrome and can cause diverse phenotypes. Thus, individuals with DOORS syndrome without deafness and seizures but with the other features should still be screened for TBC1D24 mutations. More information is needed to understand the cellular roles of TBC1D24 and identify the genes responsible for DOORS phenotypes in individuals who do not have a mutation in TBC1D24. FUNDING: US National Institutes of Health, the CIHR (Canada), the NIHR (UK), the Wellcome Trust, the Henry Smith Charity, and Action Medical Research.
Keywords: Adolescent; Carrier Proteins; Child; Child, Preschool; Craniofacial Abnormalities; Exome; Female; Hand Deformities, Congenital; Hearing Loss, Sensorineural; Humans; Infant; Intellectual Disability; Internationality; Male; Nails, Malformed; Phenotype; Sequence Analysis, DNA; Young Adult

Germ-line and somatic DICER1 mutations in pineoblastoma. - de Kock, Leanne; Sabbaghian, Nelly; Druker, Harriet; Weber, Evan; Hamel, Nancy; Miller, Suzanne; Choong, Catherine S; Gottardo, Nicholas G; Kees, Ursula R; Rednam, Surya P; van Hest, Liselotte P; Jongmans, Marjolijn C; et al. (Acta Neuropathol, 2014)
Germ-line RB-1 mutations predispose to pineoblastoma (PinB), but other predisposing genetic factors are not well established. We recently identified a germ-line DICER1 mutation in a child with a PinB. This was accompanied by loss of heterozygosity (LOH) of the wild-type allele within the tumour. We set out to establish the prevalence of DICER1 mutations in an opportunistically ascertained series of PinBs. Twenty-one PinB cases were studied: Eighteen cases had not undergone previous testing for DICER1 mutations; three patients were known carriers of germ-line DICER1 mutations. The eighteen PinBs were sequenced by Sanger and/or Fluidigm-based next-generation sequencing to identify DICER1 mutations in blood gDNA and/or tumour gDNA. Testing for somatic DICER1 mutations was also conducted on one case with a known germ-line DICER1 mutation. From the eighteen PinBs, we identified four deleterious DICER1 mutations, three of which were germ line in origin, and one for which a germ line versus somatic origin could not be determined; in all four, the second allele was also inactivated leading to complete loss of DICER1 protein. No somatic DICER1 RNase IIIb mutations were identified. One PinB arising in a germ-line DICER1 mutation carrier was found to have LOH. This study suggests that germ-line DICER1 mutations make a clinically significant contribution to PinB, establishing DICER1 as an important susceptibility gene for PinB and demonstrates PinB to be a manifestation of a germ-line DICER1 mutation. The means by which the second allele is inactivated may differ from other DICER1-related tumours.
Keywords: Adolescent; Brain Neoplasms; Child; Child, Preschool; DEAD-box RNA Helicases; DNA Mutational Analysis; Family Health; Female; Germ-Line Mutation; Humans; Infant; Male; Pineal Gland; Pinealoma; Ribonuclease III; Young Adult

Gigantism and acromegaly due to Xq26 microduplications and GPR101 mutation. - Trivellin, Giampaolo; Daly, Adrian F; Faucz, Fabio R; Yuan, Bo; Rostomyan, Liliya; Larco, Darwin O; Schernthaner-Reiter, Marie Helene; Szarek, Eva; Leal, Letícia F; Caberg, Jean-Hubert; Castermans, Emilie; Villa, Chiara; et al. (N Engl J Med, 2014)
BACKGROUND: Increased secretion of growth hormone leads to gigantism in children and acromegaly in adults; the genetic causes of gigantism and acromegaly are poorly understood. METHODS: We performed clinical and genetic studies of samples obtained from 43 patients with gigantism and then sequenced an implicated gene in samples from 248 patients with acromegaly. RESULTS: We observed microduplication on chromosome Xq26.3 in samples from 13 patients with gigantism; of these samples, 4 were obtained from members of two unrelated kindreds, and 9 were from patients with sporadic cases. All the patients had disease onset during early childhood. Of the patients with gigantism who did not carry an Xq26.3 microduplication, none presented before the age of 5 years. Genomic characterization of the Xq26.3 region suggests that the microduplications are generated during chromosome replication and that they contain four protein-coding genes. Only one of these genes, GPR101, which encodes a G-protein-coupled receptor, was overexpressed in patients' pituitary lesions. We identified a recurrent GPR101 mutation (p.E308D) in 11 of 248 patients with acromegaly, with the mutation found mostly in tumors. When the mutation was transfected into rat GH3 cells, it led to increased release of growth hormone and proliferation of growth hormone-producing cells. CONCLUSIONS: We describe a pediatric disorder (which we have termed X-linked acrogigantism [X-LAG]) that is caused by an Xq26.3 genomic duplication and is characterized by early-onset gigantism resulting from an excess of growth hormone. Duplication of GPR101 probably causes X-LAG. We also found a recurrent mutation in GPR101 in some adults with acromegaly. (Funded by the Eunice Kennedy Shriver National Institute of Child Health and Human Development and others.).
Keywords: Acromegaly; Adolescent; Adult; Age of Onset; Child; Child, Preschool; Chromosome Duplication; Chromosomes, Human, X; Female; Gigantism; Human Growth Hormone; Humans; Infant; Male; Mutation; Phenotype; Protein Conformation; Receptors, G-Protein-Coupled

Heterozygous de novo and inherited mutations in the smooth muscle actin (ACTG2) gene underlie megacystis-microcolon-intestinal hypoperistalsis syndrome. - Wangler, Michael F; Gonzaga-Jauregui, Claudia; Gambin, Tomasz; Penney, Samantha; Moss, Timothy; Chopra, Atul; Probst, Frank J; Xia, Fan; Yang, Yaping; Werlin, Steven; Eglite, Ieva; Kornejeva, Liene; et al. (PLoS Genet, 2014)
Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a rare disorder of enteric smooth muscle function affecting the intestine and bladder. Patients with this severe phenotype are dependent on total parenteral nutrition and urinary catheterization. The cause of this syndrome has remained a mystery since Berdon's initial description in 1976. No genes have been clearly linked to MMIHS. We used whole-exome sequencing for gene discovery followed by targeted Sanger sequencing in a cohort of patients with MMIHS and intestinal pseudo-obstruction. We identified heterozygous ACTG2 missense variants in 15 unrelated subjects, ten being apparent de novo mutations. Ten unique variants were detected, of which six affected CpG dinucleotides and resulted in missense mutations at arginine residues, perhaps related to biased usage of CpG containing codons within actin genes. We also found some of the same heterozygous mutations that we observed as apparent de novo mutations in MMIHS segregating in families with intestinal pseudo-obstruction, suggesting that ACTG2 is responsible for a spectrum of smooth muscle disease. ACTG2 encodes γ2 enteric actin and is the first gene to be clearly associated with MMIHS, suggesting an important role for contractile proteins in enteric smooth muscle disease.
Keywords: Abnormalities, Multiple; Actins; Adolescent; Adult; Child; Child, Preschool; Colon; Exome; Female; Heterozygote; Humans; Intestinal Pseudo-Obstruction; Male; Muscle, Smooth; Mutation; Urinary Bladder

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; Transcription Factors

Increased frequency of de novo copy number variants in congenital heart disease by integrative analysis of single nucleotide polymorphism array and exome sequence data. - Glessner, Joseph T; Bick, Alexander G; Ito, Kaoru; Homsy, Jason; Rodriguez-Murillo, Laura; Fromer, Menachem; Mazaika, Erica; Vardarajan, Badri; Italia, Michael; Leipzig, Jeremy; DePalma, Steven R; Golhar, Ryan; et al. (Circ Res, 2014)
RATIONALE: Congenital heart disease (CHD) is among the most common birth defects. Most cases are of unknown pathogenesis. OBJECTIVE: To determine the contribution of de novo copy number variants (CNVs) in the pathogenesis of sporadic CHD. METHODS AND RESULTS: We studied 538 CHD trios using genome-wide dense single nucleotide polymorphism arrays and whole exome sequencing. Results were experimentally validated using digital droplet polymerase chain reaction. We compared validated CNVs in CHD cases with CNVs in 1301 healthy control trios. The 2 complementary high-resolution technologies identified 63 validated de novo CNVs in 51 CHD cases. A significant increase in CNV burden was observed when comparing CHD trios with healthy trios, using either single nucleotide polymorphism array (P=7×10(-5); odds ratio, 4.6) or whole exome sequencing data (P=6×10(-4); odds ratio, 3.5) and remained after removing 16% of de novo CNV loci previously reported as pathogenic (P=0.02; odds ratio, 2.7). We observed recurrent de novo CNVs on 15q11.2 encompassing CYFIP1, NIPA1, and NIPA2 and single de novo CNVs encompassing DUSP1, JUN, JUP, MED15, MED9, PTPRE SREBF1, TOP2A, and ZEB2, genes that interact with established CHD proteins NKX2-5 and GATA4. Integrating de novo variants in whole exome sequencing and CNV data suggests that ETS1 is the pathogenic gene altered by 11q24.2-q25 deletions in Jacobsen syndrome and that CTBP2 is the pathogenic gene in 10q subtelomeric deletions. CONCLUSIONS: We demonstrate a significantly increased frequency of rare de novo CNVs in CHD patients compared with healthy controls and suggest several novel genetic loci for CHD.
Keywords: Case-Control Studies; Cohort Studies; DNA Copy Number Variations; Exome; Gene Frequency; Gene Regulatory Networks; Heart Defects, Congenital; Humans; Molecular Sequence Data; Polymorphism, Single Nucleotide

Individual exome analysis in diagnosis and management of paediatric liver failure of indeterminate aetiology. - Vilarinho, Sílvia; Choi, Murim; Jain, Dhanpat; Malhotra, Ajay; Kulkarni, Sanjay; Pashankar, Dinesh; Phatak, Uma; Patel, Mohini; Bale, Allen; Mane, Shrikant; Lifton, Richard P; Mistry, Pramod K (J Hepatol, 2014)
BACKGROUND & AIMS: In children with liver failure, as many as half remain of indeterminate aetiology. This hinders timely consideration of optimal treatment options. We posit that a significant subset of these children harbour known inherited metabolic liver diseases with atypical presentation or novel inborn errors of metabolism. We investigated the utility of whole-exome sequencing in three children with advanced liver disease of indeterminate aetiology. METHODS: Patient 1 was a 10 year-old female diagnosed with Wilson disease but no detectable ATP7B mutations, and decompensated liver cirrhosis who underwent liver transplant and subsequently developed onset of neurodegenerative disease. Patient 2 was a full-term 2 day-old male with fatal acute liver failure of indeterminate aetiology. Patient 3 was an 8 year-old female with progressive syndromic cholestasis of unknown aetiology since age 3 months. RESULTS: Unbiased whole-exome sequencing of germline DNA revealed homozygous mutations in MPV17 and SERAC1 as the disease causing genes in patient 1 and 2, respectively. This is the first demonstration of SERAC1 loss-of-function associated fatal acute liver failure. Patient 1 expands the phenotypic spectrum of the MPV17-related hepatocerebral mitochondrial DNA depletion syndrome. Patient 3 was found to have syndromic cholestasis due to bi-allelic NOTCH2 mutations. CONCLUSIONS: Our findings validate the application of whole-exome sequencing in the diagnosis and management of children with advanced liver disease of indeterminate aetiology, with the potential to enhance optimal selection of treatment options and adequate counselling of families. Moreover, whole-exome sequencing revealed a hitherto unrecognized phenotypic spectrum of inherited metabolic liver diseases.
Keywords: Amino Acid Sequence; Base Sequence; Carboxylic Ester Hydrolases; Child; Cholestasis; DNA Mutational Analysis; End Stage Liver Disease; Exome; Fatal Outcome; Female; Genes, Recessive; Hepatolenticular Degeneration; Heterozygote; Homozygote; Humans; Infant, Newborn; Liver Failure; Liver Failure, Acute; Male; Membrane Proteins; Mitochondrial Proteins; Molecular Sequence Data; Pedigree; Receptor, Notch2; RNA Splice Sites; Sequence Homology, Amino Acid

Informed consent for exome sequencing research in families with genetic disease: the emerging issue of incidental findings. - Bergner, Amanda L; Bollinger, Juli; Raraigh, Karen S; Tichnell, Crystal; Murray, Brittney; Blout, Carrie Lynn; Telegrafi, Aida Bytyci; James, Cynthia A (Am J Med Genet A, 2014)
Genomic sequencing technology is increasingly used in genetic research. Studies of informed consent for exome and genome sequencing (ES/GS) research have largely involved hypothetical scenarios or healthy individuals enrolling in population-based studies. Studies have yet to explore the consent experiences of adults with inherited disease. We conducted a qualitative interview study of 15 adults recently enrolled in a large-scale ES/GS study (11 affected adults, four parents of affected children). Our study had two goals: (1) to explore three theoretical barriers to consent for ES/GS research (interpretive/technical complexity, possibility of incidental findings, and risks of loss of privacy); and (2) to explore how interviewees experienced the consent process. Interviewees could articulate study goals and processes, describe incidental findings, discuss risks of privacy loss, and reflect on their consent experience. Few expected the study would identify the genetic cause of their condition. All elected to receive incidental findings. Interviewees acknowledged paying little attention to potential implications of incidental findings in light of more pressing goals of supporting research regarding their own medical conditions. Interviewees suggested that experience living with a genetic condition prepared them to adjust to incidental findings. Interviewees also expressed little concern about loss of confidentiality of study data. Some experienced the consent process as very long. None desired reconsent prior to return of study results. Families with inherited disease likely would benefit from a consent process in which study risks and benefits were discussed in the context of prior experiences with genetic research and genetic disease.
Keywords: Adolescent; Adult; Aged; Confidentiality; Ethics, Medical; Exome; Family; Female; Genetic Diseases, Inborn; Genetic Research; High-Throughput Nucleotide Sequencing; Humans; Incidental Findings; Informed Consent; Male; Middle Aged; Young Adult

Laterality defects other than situs inversus totalis in primary ciliary dyskinesia: insights into situs ambiguus and heterotaxy. - Shapiro, Adam J; Davis, Stephanie D; Ferkol, Thomas; Dell, Sharon D; Rosenfeld, Margaret; Olivier, Kenneth N; Sagel, Scott D; Milla, Carlos; Zariwala, Maimoona A; Wolf, Whitney; Carson, Johnny L; Hazucha, Milan J; et al. (Chest, 2014)
BACKGROUND: Motile cilia dysfunction causes primary ciliary dyskinesia (PCD), situs inversus totalis (SI), and a spectrum of laterality defects, yet the prevalence of laterality defects other than SI in PCD has not been prospectively studied. METHODS: In this prospective study, participants with suspected PCD were referred to our multisite consortium. We measured nasal nitric oxide (nNO) level, examined cilia with electron microscopy, and analyzed PCD-causing gene mutations. Situs was classified as (1) situs solitus (SS), (2) SI, or (3) situs ambiguus (SA), including heterotaxy. Participants with hallmark electron microscopic defects, biallelic gene mutations, or both were considered to have classic PCD. RESULTS: Of 767 participants (median age, 8.1 years, range, 0.1-58 years), classic PCD was defined in 305, including 143 (46.9%), 125 (41.0%), and 37 (12.1%) with SS, SI, and SA, respectively. A spectrum of laterality defects was identified with classic PCD, including 2.6% and 2.3% with SA plus complex or simple cardiac defects, respectively; 4.6% with SA but no cardiac defect; and 2.6% with an isolated possible laterality defect. Participants with SA and classic PCD had a higher prevalence of PCD-associated respiratory symptoms vs SA control participants (year-round wet cough, P < .001; year-round nasal congestion, P = .015; neonatal respiratory distress, P = .009; digital clubbing, P = .021) and lower nNO levels (median, 12 nL/min vs 252 nL/min; P < .001). CONCLUSIONS: At least 12.1% of patients with classic PCD have SA and laterality defects ranging from classic heterotaxy to subtle laterality defects. Specific clinical features of PCD and low nNO levels help to identify PCD in patients with laterality defects. TRIAL REGISTRY: ClinicalTrials.gov; No.: NCT00323167; URL: www.clinicaltrials.gov.
Keywords: Adolescent; Adult; Biopsy; Child; Child, Preschool; Cilia; DNA; DNA Mutational Analysis; Female; Humans; Infant; Infant, Newborn; Kartagener Syndrome; Male; Microscopy, Electron, Transmission; Middle Aged; Mutation; Prevalence; Prospective Studies; Tomography, X-Ray Computed; United States; Young Adult

Launching genomics into the cloud: deployment of Mercury, a next generation sequence analysis pipeline. - Reid, Jeffrey G; Carroll, Andrew; Veeraraghavan, Narayanan; Dahdouli, Mahmoud; Sundquist, Andreas; English, Adam; Bainbridge, Matthew; White, Simon; Salerno, William; Buhay, Christian; Yu, Fuli; Muzny, Donna; et al. (BMC Bioinformatics, 2014)
BACKGROUND: Massively parallel DNA sequencing generates staggering amounts of data. Decreasing cost, increasing throughput, and improved annotation have expanded the diversity of genomics applications in research and clinical practice. This expanding scale creates analytical challenges: accommodating peak compute demand, coordinating secure access for multiple analysts, and sharing validated tools and results. RESULTS: To address these challenges, we have developed the Mercury analysis pipeline and deployed it in local hardware and the Amazon Web Services cloud via the DNAnexus platform. Mercury is an automated, flexible, and extensible analysis workflow that provides accurate and reproducible genomic results at scales ranging from individuals to large cohorts. CONCLUSIONS: By taking advantage of cloud computing and with Mercury implemented on the DNAnexus platform, we have demonstrated a powerful combination of a robust and fully validated software pipeline and a scalable computational resource that, to date, we have applied to more than 10,000 whole genome and whole exome samples.
Keywords: Genome; Genomics; High-Throughput Nucleotide Sequencing; Humans; Internet; Software

Loss-of-function HDAC8 mutations cause a phenotypic spectrum of Cornelia de Lange syndrome-like features, ocular hypertelorism, large fontanelle and X-linked inheritance. - Kaiser, Frank J; Ansari, Morad; Braunholz, Diana; Concepción Gil-Rodríguez, María; Decroos, Christophe; Wilde, Jonathan J; Fincher, Christopher T; Kaur, Maninder; Bando, Masashige; Amor, David J; Atwal, Paldeep S; Bahlo, Melanie; et al. (Hum Mol Genet, 2014)
Cornelia de Lange syndrome (CdLS) is a multisystem genetic disorder with distinct facies, growth failure, intellectual disability, distal limb anomalies, gastrointestinal and neurological disease. Mutations in NIPBL, encoding a cohesin regulatory protein, account for >80% of cases with typical facies. Mutations in the core cohesin complex proteins, encoded by the SMC1A, SMC3 and RAD21 genes, together account for ∼5% of subjects, often with atypical CdLS features. Recently, we identified mutations in the X-linked gene HDAC8 as the cause of a small number of CdLS cases. Here, we report a cohort of 38 individuals with an emerging spectrum of features caused by HDAC8 mutations. For several individuals, the diagnosis of CdLS was not considered prior to genomic testing. Most mutations identified are missense and de novo. Many cases are heterozygous females, each with marked skewing of X-inactivation in peripheral blood DNA. We also identified eight hemizygous males who are more severely affected. The craniofacial appearance caused by HDAC8 mutations overlaps that of typical CdLS but often displays delayed anterior fontanelle closure, ocular hypertelorism, hooding of the eyelids, a broader nose and dental anomalies, which may be useful discriminating features. HDAC8 encodes the lysine deacetylase for the cohesin subunit SMC3 and analysis of the functional consequences of the missense mutations indicates that all cause a loss of enzymatic function. These data demonstrate that loss-of-function mutations in HDAC8 cause a range of overlapping human developmental phenotypes, including a phenotypically distinct subgroup of CdLS.
Keywords: Amino Acid Sequence; Child; Child, Preschool; Cohort Studies; Cranial Fontanelles; De Lange Syndrome; Eye Abnormalities; Female; Genes, X-Linked; Histone Deacetylases; Humans; Hypertelorism; Infant; Male; Molecular Sequence Data; Mutation, Missense; Phenotype; Repressor Proteins; Sequence Alignment

Microcephaly, epilepsy, and neonatal diabetes due to compound heterozygous mutations in IER3IP1: insights into the natural history of a rare disorder. - Shalev, Stavit A; Tenenbaum-Rakover, Yardena; Horovitz, Yoseph; Paz, Veronica P; Ye, Honggang; Carmody, David; Highland, Heather M; Boerwinkle, Eric; Hanis, Craig L; Muzny, Donna M; Gibbs, Richard A; Bell, Graeme I; et al. (Pediatr Diabetes, 2014)
Neonatal diabetes mellitus is known to have over 20 different monogenic causes. A syndrome of permanent neonatal diabetes along with primary microcephaly with simplified gyral pattern associated with severe infantile epileptic encephalopathy was recently described in two independent reports in which disease-causing homozygous mutations were identified in the immediate early response-3 interacting protein-1 (IER3IP1) gene. We report here an affected male born to a non-consanguineous couple who was noted to have insulin-requiring permanent neonatal diabetes, microcephaly, and generalized seizures. He was also found to have cortical blindness, severe developmental delay and numerous dysmorphic features. He experienced a slow improvement but not abrogation of seizure frequency and severity on numerous anti-epileptic agents. His clinical course was further complicated by recurrent respiratory tract infections and he died at 8 years of age. Whole exome sequencing was performed on DNA from the proband and parents. He was found to be a compound heterozygote with two different mutations in IER3IP1: p.Val21Gly (V21G) and a novel frameshift mutation p.Phe27fsSer*25. IER3IP1 is a highly conserved protein with marked expression in the cerebral cortex and in beta cells. This is the first reported case of compound heterozygous mutations within IER3IP1 resulting in neonatal diabetes. The triad of microcephaly, generalized seizures, and permanent neonatal diabetes should prompt screening for mutations in IER3IP1. As mutations in genes such as NEUROD1 and PTF1A could cause a similar phenotype, next-generation sequencing approaches-such as exome sequencing reported here-may be an efficient means of uncovering a diagnosis in future cases.
Keywords: Amino Acid Substitution; Blindness, Cortical; Carrier Proteins; Developmental Disabilities; Diabetes Mellitus; Epilepsy, Generalized; Fatal Outcome; Frameshift Mutation; Heterozygote; Humans; Infant, Newborn; Infant, Newborn, Diseases; Male; Membrane Proteins; Microcephaly; Neurologic Manifestations; Point Mutation; Severity of Illness Index

Molecular findings among patients referred for clinical whole-exome sequencing. - Yang, Yaping; Muzny, Donna M; Xia, Fan; Niu, Zhiyv; Person, Richard; Ding, Yan; Ward, Patricia; Braxton, Alicia; Wang, Min; Buhay, Christian; Veeraraghavan, Narayanan; Hawes, Alicia; et al. (JAMA, 2014)
IMPORTANCE: Clinical whole-exome sequencing is increasingly used for diagnostic evaluation of patients with suspected genetic disorders. OBJECTIVE: To perform clinical whole-exome sequencing and report (1) the rate of molecular diagnosis among phenotypic groups, (2) the spectrum of genetic alterations contributing to disease, and (3) the prevalence of medically actionable incidental findings such as FBN1 mutations causing Marfan syndrome. DESIGN, SETTING, AND PATIENTS: Observational study of 2000 consecutive patients with clinical whole-exome sequencing analyzed between June 2012 and August 2014. Whole-exome sequencing tests were performed at a clinical genetics laboratory in the United States. Results were reported by clinical molecular geneticists certified by the American Board of Medical Genetics and Genomics. Tests were ordered by the patient's physician. The patients were primarily pediatric (1756 [88%]; mean age, 6 years; 888 females [44%], 1101 males [55%], and 11 fetuses [1% gender unknown]), demonstrating diverse clinical manifestations most often including nervous system dysfunction such as developmental delay. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing diagnosis rate overall and by phenotypic category, mode of inheritance, spectrum of genetic events, and reporting of incidental findings. RESULTS: A molecular diagnosis was reported for 504 patients (25.2%) with 58% of the diagnostic mutations not previously reported. Molecular diagnosis rates for each phenotypic category were 143/526 (27.2%; 95% CI, 23.5%-31.2%) for the neurological group, 282/1147 (24.6%; 95% CI, 22.1%-27.2%) for the neurological plus other organ systems group, 30/83 (36.1%; 95% CI, 26.1%-47.5%) for the specific neurological group, and 49/244 (20.1%; 95% CI, 15.6%-25.8%) for the nonneurological group. The Mendelian disease patterns of the 527 molecular diagnoses included 280 (53.1%) autosomal dominant, 181 (34.3%) autosomal recessive (including 5 with uniparental disomy), 65 (12.3%) X-linked, and 1 (0.2%) mitochondrial. Of 504 patients with a molecular diagnosis, 23 (4.6%) had blended phenotypes resulting from 2 single gene defects. About 30% of the positive cases harbored mutations in disease genes reported since 2011. There were 95 medically actionable incidental findings in genes unrelated to the phenotype but with immediate implications for management in 92 patients (4.6%), including 59 patients (3%) with mutations in genes recommended for reporting by the American College of Medical Genetics and Genomics. CONCLUSIONS AND RELEVANCE: Whole-exome sequencing provided a potential molecular diagnosis for 25% of a large cohort of patients referred for evaluation of suspected genetic conditions, including detection of rare genetic events and new mutations contributing to disease. The yield of whole-exome sequencing may offer advantages over traditional molecular diagnostic approaches in certain patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Fetus; Genetic Diseases, Inborn; Genetic Testing; Genomics; Humans; Incidental Findings; Infant; Infant, Newborn; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Referral and Consultation; Sequence Analysis, DNA

Monoallelic and biallelic mutations in MAB21L2 cause a spectrum of major eye malformations. - Rainger, Joe; Pehlivan, Davut; Johansson, Stefan; Bengani, Hemant; Sanchez-Pulido, Luis; Williamson, Kathleen A; Ture, Mehmet; Barker, Heather; Rosendahl, Karen; Spranger, Jürgen; Horn, Denise; Meynert, Alison; et al. (Am J Hum Genet, 2014)
We identified four different missense mutations in the single-exon gene MAB21L2 in eight individuals with bilateral eye malformations from five unrelated families via three independent exome sequencing projects. Three mutational events altered the same amino acid (Arg51), and two were identical de novo mutations (c.151C>T [p.Arg51Cys]) in unrelated children with bilateral anophthalmia, intellectual disability, and rhizomelic skeletal dysplasia. c.152G>A (p.Arg51His) segregated with autosomal-dominant bilateral colobomatous microphthalmia in a large multiplex family. The fourth heterozygous mutation (c.145G>A [p.Glu49Lys]) affected an amino acid within two residues of Arg51 in an adult male with bilateral colobomata. In a fifth family, a homozygous mutation (c.740G>A [p.Arg247Gln]) altering a different region of the protein was identified in two male siblings with bilateral retinal colobomata. In mouse embryos, Mab21l2 showed strong expression in the developing eye, pharyngeal arches, and limb bud. As predicted by structural homology, wild-type MAB21L2 bound single-stranded RNA, whereas this activity was lost in all altered forms of the protein. MAB21L2 had no detectable nucleotidyltransferase activity in vitro, and its function remains unknown. Induced expression of wild-type MAB21L2 in human embryonic kidney 293 cells increased phospho-ERK (pERK1/2) signaling. Compared to the wild-type and p.Arg247Gln proteins, the proteins with the Glu49 and Arg51 variants had increased stability. Abnormal persistence of pERK1/2 signaling in MAB21L2-expressing cells during development is a plausible pathogenic mechanism for the heterozygous mutations. The phenotype associated with the homozygous mutation might be a consequence of complete loss of MAB21L2 RNA binding, although the cellular function of this interaction remains unknown.
Keywords: Adult; Alleles; Animals; Anophthalmos; Brain Diseases, Metabolic, Inborn; Coloboma; Corneal Opacity; Exome; Eye Proteins; Female; Gene Expression; HEK293 Cells; Heterozygote; Homozygote; Humans; Intellectual Disability; Intracellular Signaling Peptides and Proteins; Male; Mice; Microcephaly; Microphthalmos; Mutation, Missense; Pedigree; Phenotype; Protein Conformation; Signal Transduction

Multilineage somatic activating mutations in HRAS and NRAS cause mosaic cutaneous and skeletal lesions, elevated FGF23 and hypophosphatemia. - Lim, Young H; Ovejero, Diana; Sugarman, Jeffrey S; Deklotz, Cynthia M C; Maruri, Ann; Eichenfield, Lawrence F; Kelley, Patrick K; Jüppner, Harald; Gottschalk, Michael; Tifft, Cynthia J; Gafni, Rachel I; Boyce, Alison M; et al. (Hum Mol Genet, 2014)
Pathologically elevated serum levels of fibroblast growth factor-23 (FGF23), a bone-derived hormone that regulates phosphorus homeostasis, result in renal phosphate wasting and lead to rickets or osteomalacia. Rarely, elevated serum FGF23 levels are found in association with mosaic cutaneous disorders that affect large proportions of the skin and appear in patterns corresponding to the migration of ectodermal progenitors. The cause and source of elevated serum FGF23 is unknown. In those conditions, such as epidermal and large congenital melanocytic nevi, skin lesions are variably associated with other abnormalities in the eye, brain and vasculature. The wide distribution of involved tissues and the appearance of multiple segmental skin and bone lesions suggest that these conditions result from early embryonic somatic mutations. We report five such cases with elevated serum FGF23 and bone lesions, four with large epidermal nevi and one with a giant congenital melanocytic nevus. Exome sequencing of blood and affected skin tissue identified somatic activating mutations of HRAS or NRAS in each case without recurrent secondary mutation, and we further found that the same mutation is present in dysplastic bone. Our finding of somatic activating RAS mutation in bone, the endogenous source of FGF23, provides the first evidence that elevated serum FGF23 levels, hypophosphatemia and osteomalacia are associated with pathologic Ras activation and may provide insight in the heretofore limited understanding of the regulation of FGF23.
Keywords: Adolescent; Child; Exome; Female; Fibroblast Growth Factors; Gene Expression Regulation, Developmental; GTP Phosphohydrolases; Humans; Hypophosphatemia; Male; Membrane Proteins; Mutation; Nevus; Nevus, Pigmented; Osteomalacia; Proto-Oncogene Proteins p21(ras); Sequence Analysis, DNA; Skin; Skin Neoplasms

Mutation of NLRC4 causes a syndrome of enterocolitis and autoinflammation. - Romberg, Neil; Al Moussawi, Khatoun; Nelson-Williams, Carol; Stiegler, Amy L; Loring, Erin; Choi, Murim; Overton, John; Meffre, Eric; Khokha, Mustafa K; Huttner, Anita J; West, Brian; Podoltsev, Nikolai A; et al. (Nat Genet, 2014)
Upon detection of pathogen-associated molecular patterns, innate immune receptors initiate inflammatory responses. These receptors include cytoplasmic NOD-like receptors (NLRs) whose stimulation recruits and proteolytically activates caspase-1 within the inflammasome, a multiprotein complex. Caspase-1 mediates the production of interleukin-1 family cytokines (IL1FCs), leading to fever and inflammatory cell death (pyroptosis). Mutations that constitutively activate these pathways underlie several autoinflammatory diseases with diverse clinical features. We describe a family with a previously unreported syndrome featuring neonatal-onset enterocolitis, periodic fever, and fatal or near-fatal episodes of autoinflammation. We show that the disease is caused by a de novo gain-of-function mutation in NLRC4 encoding a p.Val341Ala substitution in the HD1 domain of the protein that cosegregates with disease. Mutant NLRC4 causes constitutive IL1FC production and macrophage cell death. Infected macrophages from affected individuals are polarized toward pyroptosis and exhibit abnormal staining for inflammasome components. These findings identify and describe the cause of a life-threatening but treatable autoinflammatory disease that underscores the divergent roles of the NLRC4 inflammasome.
Keywords: Calcium-Binding Proteins; CARD Signaling Adaptor Proteins; Enterocolitis; Exome; Family Health; Fatal Outcome; Female; Humans; Inflammation; Male; Mutation, Missense; Pedigree; Sequence Analysis, DNA; Syndrome

Mutations in Alström protein impair terminal differentiation of cardiomyocytes. - Shenje, Lincoln T; Andersen, Peter; Halushka, Marc K; Lui, Cecillia; Fernandez, Laviel; Collin, Gayle B; Amat-Alarcon, Nuria; Meschino, Wendy; Cutz, Ernest; Chang, Kenneth; Yonescu, Raluca; Batista, Denise A S; et al. (Nat Commun, 2014)
Cardiomyocyte cell division and replication in mammals proceed through embryonic development and abruptly decline soon after birth. The process governing cardiomyocyte cell cycle arrest is poorly understood. Here we carry out whole-exome sequencing in an infant with evidence of persistent postnatal cardiomyocyte replication to determine the genetic risk factors. We identify compound heterozygous ALMS1 mutations in the proband, and confirm their presence in her affected sibling, one copy inherited from each heterozygous parent. Next, we recognize homozygous or compound heterozygous truncating mutations in ALMS1 in four other children with high levels of postnatal cardiomyocyte proliferation. Alms1 mRNA knockdown increases multiple markers of proliferation in cardiomyocytes, the percentage of cardiomyocytes in G2/M phases, and the number of cardiomyocytes by 10% in cultured cells. Homozygous Alms1-mutant mice have increased cardiomyocyte proliferation at 2 weeks postnatal compared with wild-type littermates. We conclude that deficiency of Alström protein impairs postnatal cardiomyocyte cell cycle arrest.
Keywords: Animals; Cell Cycle; Cell Differentiation; Cells, Cultured; DNA-Binding Proteins; Humans; Immunohistochemistry; Mice; Molecular Sequence Data; Mutation; Myocytes, Cardiac; Proteins; Reverse Transcriptase Polymerase Chain Reaction

Mutations in CSPP1 lead to classical Joubert syndrome. - Akizu, Naiara; Silhavy, Jennifer L; Rosti, Rasim Ozgur; Scott, Eric; Fenstermaker, Ali G; Schroth, Jana; Zaki, Maha S; Sanchez, Henry; Gupta, Neerja; Kabra, Madhulika; Kara, Majdi; Ben-Omran, Tawfeg; et al. (Am J Hum Genet, 2014)
Joubert syndrome and related disorders (JSRDs) are genetically heterogeneous and characterized by a distinctive mid-hindbrain malformation. Causative mutations lead to primary cilia dysfunction, which often results in variable involvement of other organs such as the liver, retina, and kidney. We identified predicted null mutations in CSPP1 in six individuals affected by classical JSRDs. CSPP1 encodes a protein localized to centrosomes and spindle poles, as well as to the primary cilium. Despite the known interaction between CSPP1 and nephronophthisis-associated proteins, none of the affected individuals in our cohort presented with kidney disease, and further, screening of a large cohort of individuals with nephronophthisis demonstrated no mutations. CSPP1 is broadly expressed in neural tissue, and its encoded protein localizes to the primary cilium in an in vitro model of human neurogenesis. Here, we show abrogated protein levels and ciliogenesis in affected fibroblasts. Our data thus suggest that CSPP1 is involved in neural-specific functions of primary cilia.
Keywords: Abnormalities, Multiple; Brain; Cell Cycle Proteins; Centrosome; Cerebellar Diseases; Cerebellum; Cilia; Cohort Studies; Eye Abnormalities; Fibroblasts; Gene Deletion; Humans; Image Processing, Computer-Assisted; Kidney Diseases, Cystic; Microtubule-Associated Proteins; Polymorphism, Single Nucleotide; Retina

Mutations in KATNB1 cause complex cerebral malformations by disrupting asymmetrically dividing neural progenitors. - Mishra-Gorur, Ketu; Çağlayan, Ahmet Okay; Schaffer, Ashleigh E; Chabu, Chiswili; Henegariu, Octavian; Vonhoff, Fernando; Akgümüş, Gözde Tuğce; Nishimura, Sayoko; Han, Wenqi; Tu, Shu; Baran, Burçin; Gümüş, Hakan; et al. (Neuron, 2014)
Exome sequencing analysis of over 2,000 children with complex malformations of cortical development identified five independent (four homozygous and one compound heterozygous) deleterious mutations in KATNB1, encoding the regulatory subunit of the microtubule-severing enzyme Katanin. Mitotic spindle formation is defective in patient-derived fibroblasts, a consequence of disrupted interactions of mutant KATNB1 with KATNA1, the catalytic subunit of Katanin, and other microtubule-associated proteins. Loss of KATNB1 orthologs in zebrafish (katnb1) and flies (kat80) results in microcephaly, recapitulating the human phenotype. In the developing Drosophila optic lobe, kat80 loss specifically affects the asymmetrically dividing neuroblasts, which display supernumerary centrosomes and spindle abnormalities during mitosis, leading to cell cycle progression delays and reduced cell numbers. Furthermore, kat80 depletion results in dendritic arborization defects in sensory and motor neurons, affecting neural architecture. Taken together, we provide insight into the mechanisms by which KATNB1 mutations cause human cerebral cortical malformations, demonstrating its fundamental role during brain development.
Keywords: Adenosine Triphosphatases; Animals; Brain; Cell Count; Cell Division; Dendrites; Drosophila; Drosophila Proteins; Humans; Katanin; Mice; Microcephaly; Microtubule-Associated Proteins; Mutation; Neural Stem Cells; Neurogenesis; Optic Lobe, Nonmammalian; Spindle Apparatus; Zebrafish

Mutations in LAMA1 cause cerebellar dysplasia and cysts with and without retinal dystrophy. - Aldinger, Kimberly A; Mosca, Stephen J; Tétreault, Martine; Dempsey, Jennifer C; Ishak, Gisele E; Hartley, Taila; Phelps, Ian G; Lamont, Ryan E; O'Day, Diana R; Basel, Donald; Gripp, Karen W; Baker, Laura; et al. (Am J Hum Genet, 2014)
Cerebellar dysplasia with cysts (CDC) is an imaging finding typically seen in combination with cobblestone cortex and congenital muscular dystrophy in individuals with dystroglycanopathies. More recently, CDC was reported in seven children without neuromuscular involvement (Poretti-Boltshauser syndrome). Using a combination of homozygosity mapping and whole-exome sequencing, we identified biallelic mutations in LAMA1 as the cause of CDC in seven affected individuals (from five families) independent from those included in the phenotypic description of Poretti-Boltshauser syndrome. Most of these individuals also have high myopia, and some have retinal dystrophy and patchy increased T2-weighted fluid-attenuated inversion recovery (T2/FLAIR) signal in cortical white matter. In one additional family, we identified two siblings who have truncating LAMA1 mutations in combination with retinal dystrophy and mild cerebellar dysplasia without cysts, indicating that cysts are not an obligate feature associated with loss of LAMA1 function. This work expands the phenotypic spectrum associated with the lamininopathy disorders and highlights the tissue-specific roles played by different laminin-encoding genes.
Keywords: Adult; Alleles; Base Sequence; Cerebellar Cortex; Cerebellar Diseases; Child; Child, Preschool; Cysts; Exome; Female; Humans; Laminin; Male; Muscular Dystrophies; Retinal Dystrophies; Sequence Analysis, DNA; Young Adult

Mutations in PCYT1A, encoding a key regulator of phosphatidylcholine metabolism, cause spondylometaphyseal dysplasia with cone-rod dystrophy. - Hoover-Fong, Julie; Sobreira, Nara; Jurgens, Julie; Modaff, Peggy; Blout, Carrie; Moser, Ann; Kim, Ok-Hwa; Cho, Tae-Joon; Cho, Sung Yoon; Kim, Sang Jin; Jin, Dong-Kyu; Kitoh, Hiroshi; et al. (Am J Hum Genet, 2014)
Keywords: Alleles; Child, Preschool; Choline-Phosphate Cytidylyltransferase; Female; Humans; Infant; Male; Middle Aged; Mutation, Missense; Osteochondrodysplasias; Pedigree; Phosphatidylcholines; Retinitis Pigmentosa

Mutations in PIEZO2 cause Gordon syndrome, Marden-Walker syndrome, and distal arthrogryposis type 5. - McMillin, Margaret J; Beck, Anita E; Chong, Jessica X; Shively, Kathryn M; Buckingham, Kati J; Gildersleeve, Heidi I S; Aracena, Mariana I; Aylsworth, Arthur S; Bitoun, Pierre; Carey, John C; Clericuzio, Carol L; Crow, Yanick J; et al. (Am J Hum Genet, 2014)
Gordon syndrome (GS), or distal arthrogryposis type 3, is a rare, autosomal-dominant disorder characterized by cleft palate and congenital contractures of the hands and feet. Exome sequencing of five GS-affected families identified mutations in piezo-type mechanosensitive ion channel component 2 (PIEZO2) in each family. Sanger sequencing revealed PIEZO2 mutations in five of seven additional families studied (for a total of 10/12 [83%] individuals), and nine families had an identical c.8057G>A (p.Arg2686His) mutation. The phenotype of GS overlaps with distal arthrogryposis type 5 (DA5) and Marden-Walker syndrome (MWS). Using molecular inversion probes for targeted sequencing to screen PIEZO2, we found mutations in 24/29 (82%) DA5-affected families and one of two MWS-affected families. The presence of cleft palate was significantly associated with c.8057G>A (Fisher's exact test, adjusted p value < 0.0001). Collectively, although GS, DA5, and MWS have traditionally been considered separate disorders, our findings indicate that they are etiologically related and perhaps represent variable expressivity of the same condition.
Keywords: Abnormalities, Multiple; Arachnodactyly; Arthrogryposis; Blepharophimosis; Child; Child, Preschool; Cleft Palate; Clubfoot; Connective Tissue Diseases; Contracture; Exome; Female; Hand Deformities, Congenital; Humans; Ion Channels; Male; Mutation; Ophthalmoplegia; Pedigree; Retinal Diseases

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

Mutations in RSPH1 cause primary ciliary dyskinesia with a unique clinical and ciliary phenotype. - Knowles, Michael R; Ostrowski, Lawrence E; Leigh, Margaret W; Sears, Patrick R; Davis, Stephanie D; Wolf, Whitney E; Hazucha, Milan J; Carson, Johnny L; Olivier, Kenneth N; Sagel, Scott D; Rosenfeld, Margaret; Ferkol, Thomas W; et al. (Am J Respir Crit Care Med, 2014)
RATIONALE: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous recessive disorder of motile cilia, but the genetic cause is not defined for all patients with PCD. OBJECTIVES: To identify disease-causing mutations in novel genes, we performed exome sequencing, follow-up characterization, mutation scanning, and genotype-phenotype studies in patients with PCD. METHODS: Whole-exome sequencing was performed using NimbleGen capture and Illumina HiSeq sequencing. Sanger-based sequencing was used for mutation scanning, validation, and segregation analysis. MEASUREMENTS AND MAIN RESULTS: We performed exome sequencing on an affected sib-pair with normal ultrastructure in more than 85% of cilia. A homozygous splice-site mutation was detected in RSPH1 in both siblings; parents were carriers. Screening RSPH1 in 413 unrelated probands, including 325 with PCD and 88 with idiopathic bronchiectasis, revealed biallelic loss-of-function mutations in nine additional probands. Five affected siblings of probands in RSPH1 families harbored the familial mutations. The 16 individuals with RSPH1 mutations had some features of PCD; however, nasal nitric oxide levels were higher than in patients with PCD with other gene mutations (98.3 vs. 20.7 nl/min; P < 0.0003). Additionally, individuals with RSPH1 mutations had a lower prevalence (8 of 16) of neonatal respiratory distress, and later onset of daily wet cough than typical for PCD, and better lung function (FEV1), compared with 75 age- and sex-matched PCD cases (73.0 vs. 61.8, FEV1 % predicted; P = 0.043). Cilia from individuals with RSPH1 mutations had normal beat frequency (6.1 ± Hz at 25°C), but an abnormal, circular beat pattern. CONCLUSIONS: The milder clinical disease and higher nasal nitric oxide in individuals with biallelic mutations in RSPH1 provides evidence of a unique genotype-phenotype relationship in PCD, and suggests that mutations in RSPH1 may be associated with residual ciliary function.
Keywords: Adolescent; Adult; Child; Cilia; DNA Mutational Analysis; DNA-Binding Proteins; Exome; Female; Genetic Association Studies; Genetic Markers; Genetic Testing; Homozygote; Humans; Kartagener Syndrome; Linear Models; Male; Middle Aged; Mutation; Nasal Mucosa; Sequence Analysis, DNA; Young Adult

Mutations in TBC1D24, a gene associated with epilepsy, also cause nonsyndromic deafness DFNB86. - Rehman, Atteeq U; Santos-Cortez, Regie Lyn P; Morell, Robert J; Drummond, Meghan C; Ito, Taku; Lee, Kwanghyuk; Khan, Asma A; Basra, Muhammad Asim R; Wasif, Naveed; Ayub, Muhammad; Ali, Rana A; Raza, Syed I; et al. (Am J Hum Genet, 2014)
Inherited deafness is clinically and genetically heterogeneous. We recently mapped DFNB86, a locus associated with nonsyndromic deafness, to chromosome 16p. In this study, whole-exome sequencing was performed with genomic DNA from affected individuals from three large consanguineous families in which markers linked to DFNB86 segregate with profound deafness. Analyses of these data revealed homozygous mutation c.208G>T (p.Asp70Tyr) or c.878G>C (p.Arg293Pro) in TBC1D24 as the underlying cause of deafness in the three families. Sanger sequence analysis of TBC1D24 in an additional large family in which deafness segregates with DFNB86 identified the c.208G>T (p.Asp70Tyr) substitution. These mutations affect TBC1D24 amino acid residues that are conserved in orthologs ranging from fruit fly to human. Neither variant was observed in databases of single-nucleotide variants or in 634 chromosomes from ethnically matched control subjects. TBC1D24 in the mouse inner ear was immunolocalized predominantly to spiral ganglion neurons, indicating that DFNB86 deafness might be an auditory neuropathy spectrum disorder. Previously, six recessive mutations in TBC1D24 were reported to cause seizures (hearing loss was not reported) ranging in severity from epilepsy with otherwise normal development to epileptic encephalopathy resulting in childhood death. Two of our four families in which deafness segregates with mutant alleles of TBC1D24 were available for neurological examination. Cosegregation of epilepsy and deafness was not observed in these two families. Although the causal relationship between genotype and phenotype is not presently understood, our findings, combined with published data, indicate that recessive alleles of TBC1D24 can cause either epilepsy or nonsyndromic deafness.
Keywords: Alleles; Amino Acid Sequence; Carrier Proteins; Chromosomes, Human, Pair 16; Consanguinity; Deafness; Epilepsy; Exome; Exons; Female; Genes, Recessive; Genetic Loci; Genome-Wide Association Study; Heterozygote; Homozygote; Humans; Male; Molecular Sequence Data; Mutation; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; RNA, Messenger; Sequence Analysis, DNA

Mutations in TJP2 cause progressive cholestatic liver disease. - Sambrotta, Melissa; Strautnieks, Sandra; Papouli, Efterpi; Rushton, Peter; Clark, Barnaby E; Parry, David A; Logan, Clare V; Newbury, Lucy J; Kamath, Binita M; Ling, Simon; Grammatikopoulos, Tassos; Wagner, Bart E; et al. (Nat Genet, 2014)
Elucidating genetic causes of cholestasis has proved to be important in understanding the physiology and pathophysiology of the liver. Here we show that protein-truncating mutations in the tight junction protein 2 gene (TJP2) cause failure of protein localization and disruption of tight-junction structure, leading to severe cholestatic liver disease. These findings contrast with those in the embryonic-lethal knockout mouse, highlighting differences in redundancy in junctional complexes between organs and species.
Keywords: Animals; Base Sequence; Cholestasis, Intrahepatic; High-Throughput Nucleotide Sequencing; Humans; Immunoblotting; Immunohistochemistry; Mice; Mice, Knockout; Microscopy, Electron, Transmission; Models, Biological; Molecular Sequence Data; Mutation; Pedigree; Real-Time Polymerase Chain Reaction; Sequence Alignment; Species Specificity; Tight Junctions; Zonula Occludens-2 Protein

Neonatal diabetes, gallbladder agenesis, duodenal atresia, and intestinal malrotation caused by a novel homozygous mutation in RFX6. - Concepcion, Jennifer P; Reh, Christina S; Daniels, Mark; Liu, Xiaoming; Paz, Veronica P; Ye, Honggang; Highland, Heather M; Hanis, Craig L; Greeley, Siri Atma W (Pediatr Diabetes, 2014)
Recently, bi-allelic mutations in the transcription factor RFX6 were described as the cause of a rare condition characterized by neonatal diabetes with pancreatic and biliary hypoplasia and duodenal/jejunal atresia. A male infant developed severe hyperglycemia (446 mg/dL) within 24 h of birth. Acute abdominal concerns by day five necessitated exploratory surgery that revealed duodenal atresia, gallbladder agenesis, annular pancreas and intestinal malrotation. He also exhibited chronic diarrhea and feeding intolerance, cholestatic jaundice, and subsequent liver failure. He died of sepsis at four months old while awaiting liver transplantation. The phenotype of neonatal diabetes with intestinal atresia and biliary agenesis clearly pointed to RFX6 as the causative gene; indeed, whole exome sequencing revealed a novel homozygous RFX6 mutation c.779A>C; p.Lys260Thr (K260T). This missense mutation also changes the consensus 5' splice donor site before intron 7 and is thus predicted to cause disruption in splicing. Both parents, who were not known to be related, were heterozygous carriers. Targeted genetic testing based on consideration of phenotypic features may reveal a cause among the many genes now associated with heterogeneous forms of monogenic neonatal diabetes. Our study demonstrates the feasibility of using modern sequencing technology to identify one such rare cause. Continued research is needed to determine the possible cost-effectiveness of this approach, especially when clear phenotypic clues are absent. Further study of patients with RFX6 mutations should clarify its role in pancreatic, intestinal and enteroendocrine cellular development and explain features such as the diarrhea exhibited in our case.
Keywords: Abnormalities, Multiple; Congenital Abnormalities; Diabetes Mellitus, Type 1; Digestive System Abnormalities; DNA-Binding Proteins; Duodenal Obstruction; Fatal Outcome; Gallbladder; Humans; Infant; Infant, Newborn; Infant, Newborn, Diseases; Intestinal Atresia; Intestinal Volvulus; Male; Pancreas; Pancreatic Diseases; Regulatory Factor X Transcription Factors; Transcription Factors

A new congenital disorder of glycosylation caused by a mutation in SSR4, the signal sequence receptor 4 protein of the TRAP complex. - Losfeld, Marie Estelle; Ng, Bobby G; Kircher, Martin; Buckingham, Kati J; Turner, Emily H; Eroshkin, Alexey; Smith, Joshua D; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; Freeze, Hudson H (Hum Mol Genet, 2014)
Nearly 50 congenital disorders of glycosylation (CDG) are known, but many patients biochemically diagnosed with CDG do not have mutations in known genes. Here, we describe a 16-year-old male who was born with microcephaly, developed intellectual disability, gastroesophageal reflux and a seizure disorder. We identified a de novo variant in the X-linked SSR4 gene which encodes a protein of the heterotetrameric translocon-associated protein (TRAP) complex. The c.316delT causes a p.F106Sfs*53 in SSR4 and also reduces expression of other TRAP complex proteins. The glycosylation marker Glyc-ER-GFP was used to confirm the underglycosylation in fibroblasts from the patient. Overexpression of the wild-type SSR4 allele partially restores glycosylation of the marker and of the other members of the TRAP complex. This is the first evidence that the TRAP complex, which binds to the oligosaccharyltransferase complex, is directly involved in N-glycosylation.
Keywords: Adolescent; Calcium-Binding Proteins; Cells, Cultured; Chromosomes, Human, X; Congenital Disorders of Glycosylation; Glycosylation; Humans; Male; Membrane Glycoproteins; Point Mutation; Receptors, Cytoplasmic and Nuclear; Receptors, Peptide

New syndrome with retinitis pigmentosa is caused by nonsense mutations in retinol dehydrogenase RDH11. - Xie, Yajing Angela; Lee, Winston; Cai, Carolyn; Gambin, Tomasz; Nõupuu, Kalev; Sujirakul, Tharikarn; Ayuso, Carmen; Jhangiani, Shalini; Muzny, Donna; Boerwinkle, Eric; Gibbs, Richard; Greenstein, Vivienne C; et al. (Hum Mol Genet, 2014)
Retinitis pigmentosa (RP), a genetically heterogeneous group of retinopathies that occur in both non-syndromic and syndromic forms, is caused by mutations in ∼100 genes. Although recent advances in next-generation sequencing have aided in the discovery of novel RP genes, a number of the underlying contributing genes and loci remain to be identified. We investigated three siblings, born to asymptomatic parents of Italian-American descent, who each presented with atypical RP with systemic features, including facial dysmorphologies, psychomotor developmental delays recognized since early childhood, learning disabilities and short stature. RP-associated ophthalmological findings included salt-and-pepper retinopathy, attenuation of the arterioles and generalized rod-cone dysfunction as determined by almost extinguished electroretinogram in 2 of 3 siblings. Atypical for RP features included mottled macula at an early age and peripapillary sparing of the retinal pigment epithelium. Whole-exome sequencing data, queried under a recessive model of inheritance, identified compound heterozygous stop mutations, c.C199T:p.R67* and c.C322T:p.R108*, in the retinol dehydrogenase 11 (RDH11) gene, resulting in a non-functional protein, in all affected children. In summary, deleterious mutations in RDH11, an important enzyme for vision-related and systemic retinoic acid metabolism, cause a new syndrome with RP.
Keywords: Adolescent; Child; Codon, Nonsense; Female; Humans; Male; Oxidoreductases; Pedigree; Phenotype; Retinitis Pigmentosa; Syndrome; Vision Tests; Visual Acuity; Young Adult

Novel Deletion of SERPINF1 Causes Autosomal Recessive Osteogenesis Imperfecta Type VI in Two Brazilian Families. - Minillo, Renata Moldenhauer; Sobreira, Nara; de Faria Soares, Maria de Fatima; Jurgens, Julie; Ling, Hua; Hetrick, Kurt N; Doheny, Kimberly F; Valle, David; Brunoni, Decio; Perez, Ana B Alvarez (Mol Syndromol, 2014)
Autosomal recessive osteogenesis imperfecta (OI) accounts for 10% of all OI cases, and, currently, mutations in 10 genes (CRTAP, LEPRE1, PPIB, SERPINH1, FKBP10, SERPINF1, SP7, BMP1, TMEM38B, and WNT1) are known to be responsible for this form of the disease. PEDF is a secreted glycoprotein of the serpin superfamily that maintains bone homeostasis and regulates osteoid mineralization, and it is encoded by SERPINF1, currently associated with OI type VI (MIM 172860). Here, we report a consanguineous Brazilian family in which multiple individuals from at least 4 generations are affected with a severe form of OI, and we also report an unrelated individual from the same small city in Brazil with a similar but more severe phenotype. In both families the same homozygous SERPINF1 19-bp deletion was identified which is not known in the literature yet. We described intra- and interfamilial clinical and radiological phenotypic variability of OI type VI caused by the same homozygous SERPINF1 19-bp deletion and suggest a founder effect. Furthermore, the SERPINF1 genotypes/phenotypes reported so far in the literature are reviewed.

NR2F1 mutations cause optic atrophy with intellectual disability. - Bosch, Daniëlle G M; Boonstra, F Nienke; Gonzaga-Jauregui, Claudia; Xu, Mafei; de Ligt, Joep; Jhangiani, Shalini; Wiszniewski, Wojciech; Muzny, Donna M; Yntema, Helger G; Pfundt, Rolph; Vissers, Lisenka E L M; Spruijt, Liesbeth; et al. (Am J Hum Genet, 2014)
Optic nerve atrophy and hypoplasia can be primary disorders or can result from trans-synaptic degeneration arising from cerebral visual impairment (CVI). Here we report six individuals with CVI and/or optic nerve abnormalities, born after an uneventful pregnancy and delivery, who have either de novo heterozygous missense mutations in NR2F1, also known as COUP-TFI, or deletions encompassing NR2F1. All affected individuals show mild to moderate intellectual impairment. NR2F1 encodes a nuclear receptor protein that regulates transcription. A reporter assay showed that missense mutations in the zinc-finger DNA-binding domain and the putative ligand-binding domain decrease NR2F1 transcriptional activity. These findings indicate that NR2F1 plays an important role in the neurodevelopment of the visual system and that its disruption can lead to optic atrophy with intellectual disability.
Keywords: Adolescent; Adult; Amino Acid Sequence; Child; Child, Preschool; COUP Transcription Factor I; DNA-Binding Proteins; Female; Genotype; Humans; Intellectual Disability; Male; Molecular Sequence Data; Mutation, Missense; Optic Atrophy; Phenotype; Young Adult; Zinc Fingers

Opsismodysplasia resulting from an insertion mutation in the SH2 domain, which destabilizes INPPL1. - Li, Bing; Krakow, Deborah; Nickerson, Deborah A; Bamshad, Michael J; Chang, Yong; Lachman, Ralph S; Yilmaz, Alev; Kayserili, Hülya; Cohn, Daniel H (Am J Med Genet A, 2014)
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Child; Child, Preschool; Female; Humans; Infant; Molecular Sequence Data; Mutagenesis, Insertional; Mutation; Osteochondrodysplasias; Phosphatidylinositol-3,4,5-Trisphosphate 5-Phosphatases; Phosphoric Monoester Hydrolases; Protein Stability; Radiography; RNA Splice Sites; src Homology Domains

Parent of origin, mosaicism, and recurrence risk: probabilistic modeling explains the broken symmetry of transmission genetics. - Campbell, Ian M; Stewart, Jonathan R; James, Regis A; Lupski, James R; Stankiewicz, Paweł; Olofsson, Peter; Shaw, Chad A (Am J Hum Genet, 2014)
Most new mutations are observed to arise in fathers, and increasing paternal age positively correlates with the risk of new variants. Interestingly, new mutations in X-linked recessive disease show elevated familial recurrence rates. In male offspring, these mutations must be inherited from mothers. We previously developed a simulation model to consider parental mosaicism as a source of transmitted mutations. In this paper, we extend and formalize the model to provide analytical results and flexible formulas. The results implicate parent of origin and parental mosaicism as central variables in recurrence risk. Consistent with empirical data, our model predicts that more transmitted mutations arise in fathers and that this tendency increases as fathers age. Notably, the lack of expansion later in the male germline determines relatively lower variance in the proportion of mutants, which decreases with paternal age. Subsequently, observation of a transmitted mutation has less impact on the expected risk for future offspring. Conversely, for the female germline, which arrests after clonal expansion in early development, variance in the mutant proportion is higher, and observation of a transmitted mutation dramatically increases the expected risk of recurrence in another pregnancy. Parental somatic mosaicism considerably elevates risk for both parents. These findings have important implications for genetic counseling and for understanding patterns of recurrence in transmission genetics. We provide a convenient online tool and source code implementing our analytical results. These tools permit varying the underlying parameters that influence recurrence risk and could be useful for analyzing risk in diverse family structures.
Keywords: Adult; Aged; Aged, 80 and over; Chromosome Aberrations; DNA Copy Number Variations; Fathers; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Inheritance Patterns; Male; Middle Aged; Models, Theoretical; Mosaicism; Mothers; Pregnancy; Recurrence; Risk Factors; Young Adult

Parental somatic mosaicism is underrecognized and influences recurrence risk of genomic disorders. - Campbell, Ian M; Yuan, Bo; Robberecht, Caroline; Pfundt, Rolph; Szafranski, Przemyslaw; McEntagart, Meriel E; Nagamani, Sandesh C S; Erez, Ayelet; Bartnik, Magdalena; Wiśniowiecka-Kowalnik, Barbara; Plunkett, Katie S; Pursley, Amber N; et al. (Am J Hum Genet, 2014)
New human mutations are thought to originate in germ cells, thus making a recurrence of the same mutation in a sibling exceedingly rare. However, increasing sensitivity of genomic technologies has anecdotally revealed mosaicism for mutations in somatic tissues of apparently healthy parents. Such somatically mosaic parents might also have germline mosaicism that can potentially cause unexpected intergenerational recurrences. Here, we show that somatic mosaicism for transmitted mutations among parents of children with simplex genetic disease is more common than currently appreciated. Using the sensitivity of individual-specific breakpoint PCR, we prospectively screened 100 families with children affected by genomic disorders due to rare deletion copy-number variants (CNVs) determined to be de novo by clinical analysis of parental DNA. Surprisingly, we identified four cases of low-level somatic mosaicism for the transmitted CNV in DNA isolated from parental blood. Integrated probabilistic modeling of gametogenesis developed in response to our observations predicts that mutations in parental blood increase recurrence risk substantially more than parental mutations confined to the germline. Moreover, despite the fact that maternally transmitted mutations are the minority of alleles, our model suggests that sexual dimorphisms in gametogenesis result in a greater proportion of somatically mosaic transmitting mothers who are thus at increased risk of recurrence. Therefore, somatic mosaicism together with sexual differences in gametogenesis might explain a considerable fraction of unexpected recurrences of X-linked recessive disease. Overall, our results underscore an important role for somatic mosaicism and mitotic replicative mutational mechanisms in transmission genetics.
Keywords: Cell Division; DNA Copy Number Variations; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Male; Models, Genetic; Mosaicism; Mutation; Pedigree; Prospective Studies; Recurrence; Risk; Sex Characteristics; Smith-Magenis Syndrome

PGM3 mutations cause a congenital disorder of glycosylation with severe immunodeficiency and skeletal dysplasia. - Stray-Pedersen, Asbjørg; Backe, Paul H; Sorte, Hanne S; Mørkrid, Lars; Chokshi, Niti Y; Erichsen, Hans Christian; Gambin, Tomasz; Elgstøen, Katja B P; Bjørås, Magnar; Wlodarski, Marcin W; Krüger, Marcus; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2014)
Human phosphoglucomutase 3 (PGM3) catalyzes the conversion of N-acetyl-glucosamine (GlcNAc)-6-phosphate into GlcNAc-1-phosphate during the synthesis of uridine diphosphate (UDP)-GlcNAc, a sugar nucleotide critical to multiple glycosylation pathways. We identified three unrelated children with recurrent infections, congenital leukopenia including neutropenia, B and T cell lymphopenia, and progression to bone marrow failure. Whole-exome sequencing demonstrated deleterious mutations in PGM3 in all three subjects, delineating their disease to be due to an unsuspected congenital disorder of glycosylation (CDG). Functional studies of the disease-associated PGM3 variants in E. coli cells demonstrated reduced PGM3 activity for all mutants tested. Two of the three children had skeletal anomalies resembling Desbuquois dysplasia: short stature, brachydactyly, dysmorphic facial features, and intellectual disability. However, these additional features were absent in the third child, showing the clinical variability of the disease. Two children received hematopoietic stem cell transplantation of cord blood and bone marrow from matched related donors; both had successful engraftment and correction of neutropenia and lymphopenia. We define PGM3-CDG as a treatable immunodeficiency, document the power of whole-exome sequencing in gene discoveries for rare disorders, and illustrate the utility of genomic analyses in studying combined and variable phenotypes.
Keywords: Bone Diseases, Developmental; Congenital Disorders of Glycosylation; Female; Humans; Immunologic Deficiency Syndromes; Male; Mutation; Pedigree; Phosphoglucomutase

Phenotypic expansion of DGKE-associated diseases. - Westland, Rik; Bodria, Monica; Carrea, Alba; Lata, Sneh; Scolari, Francesco; Fremeaux-Bacchi, Veronique; D'Agati, Vivette D; Lifton, Richard P; Gharavi, Ali G; Ghiggeri, Gian Marco; Sanna-Cherchi, Simone (J Am Soc Nephrol, 2014)
Atypical hemolytic uremic syndrome (aHUS) is usually characterized by uncontrolled complement activation. The recent discovery of loss-of-function mutations in DGKE in patients with aHUS and normal complement levels challenged this observation. DGKE, encoding diacylglycerol kinase-ε, has not been implicated in the complement cascade but hypothetically leads to a prothrombotic state. The discovery of this novel mechanism has potential implications for the treatment of infants with aHUS, who are increasingly treated with complement blocking agents. In this study, we used homozygosity mapping and whole-exome sequencing to identify a novel truncating mutation in DGKE (p.K101X) in a consanguineous family with patients affected by thrombotic microangiopathy characterized by significant serum complement activation and consumption of the complement fraction C3. Aggressive plasma infusion therapy controlled systemic symptoms and prevented renal failure, suggesting that this treatment can significantly affect the natural history of this aggressive disease. Our study expands the clinical phenotypes associated with mutations in DGKE and challenges the benefits of complement blockade treatment in such patients. Mechanistic studies of DGKE and aHUS are, therefore, essential to the design of appropriate therapeutic strategies in patients with DGKE mutations.
Keywords: Atypical Hemolytic Uremic Syndrome; Child, Preschool; Diacylglycerol Kinase; Female; Hemolytic-Uremic Syndrome; Humans; Male; Pedigree; Phenotype

Power analysis and sample size estimation for sequence-based association studies. - Wang, Gao T; Li, Biao; Santos-Cortez, Regie P Lyn; Peng, Bo; Leal, Suzanne M (Bioinformatics, 2014)
MOTIVATION: Statistical methods have been developed to test for complex trait rare variant (RV) associations, in which variants are aggregated across a region, which is typically a gene. Power analysis and sample size estimation for sequence-based RV association studies are challenging because of the necessity to realistically model the underlying allelic architecture of complex diseases within a suitable analytical framework to assess the performance of a variety of RV association methods in an unbiased manner. SUMMARY: We developed SEQPower, a software package to perform statistical power analysis for sequence-based association data under a variety of genetic variant and disease phenotype models. It aids epidemiologists in determining the best study design, sample size and statistical tests for sequence-based association studies. It also provides biostatisticians with a platform to fairly compare RV association methods and to validate and assess novel association tests. AVAILABILITY AND IMPLEMENTATION: The SEQPower program, source code, multi-platform executables, documentation, list of association tests, examples and tutorials are available at http://bioinformatics.org/spower.
Keywords: Alleles; Data Interpretation, Statistical; Disease; Genetic Association Studies; Genetic Variation; Humans; Phenotype; Sample Size; Sequence Analysis, DNA; Software

PRIMUS: rapid reconstruction of pedigrees from genome-wide estimates of identity by descent. - Staples, Jeffrey; Qiao, Dandi; Cho, Michael H; Silverman, Edwin K; Nickerson, Deborah A; Below, Jennifer E (Am J Hum Genet, 2014)
Understanding and correctly utilizing relatedness among samples is essential for genetic analysis; however, managing sample records and pedigrees can often be error prone and incomplete. Data sets ascertained by random sampling often harbor cryptic relatedness that can be leveraged in genetic analyses for maximizing power. We have developed a method that uses genome-wide estimates of pairwise identity by descent to identify families and quickly reconstruct and score all possible pedigrees that fit the genetic data by using up to third-degree relatives, and we have included it in the software package PRIMUS (Pedigree Reconstruction and Identification of the Maximally Unrelated Set). Here, we validate its performance on simulated, clinical, and HapMap pedigrees. Among these samples, we demonstrate that PRIMUS can verify reported pedigree structures and identify cryptic relationships. Finally, we show that PRIMUS reconstructed pedigrees, all of which were previously unknown, for 203 families from a cohort collected in Starr County, TX (1,890 samples).
Keywords: Base Sequence; Computer Simulation; Exome; Gene Frequency; Genetics, Population; Humans; Molecular Sequence Data; Pedigree; Pulmonary Disease, Chronic Obstructive; Sequence Analysis, DNA; Software; Texas

Rare-variant extensions of the transmission disequilibrium test: application to autism exome sequence data. - He, Zongxiao; O'Roak, Brian J; Smith, Joshua D; Wang, Gao; Hooker, Stanley; Santos-Cortez, Regie Lyn P; Li, Biao; Kan, Mengyuan; Krumm, Nik; Nickerson, Deborah A; Shendure, Jay; Eichler, Evan E; et al. (Am J Hum Genet, 2014)
Many population-based rare-variant (RV) association tests, which aggregate variants across a region, have been developed to analyze sequence data. A drawback of analyzing population-based data is that it is difficult to adequately control for population substructure and admixture, and spurious associations can occur. For RVs, this problem can be substantial, because the spectrum of rare variation can differ greatly between populations. A solution is to analyze parent-child trio data, by using the transmission disequilibrium test (TDT), which is robust to population substructure and admixture. We extended the TDT to test for RV associations using four commonly used methods. We demonstrate that for all RV-TDT methods, using proper analysis strategies, type I error is well-controlled even when there are high levels of population substructure or admixture. For trio data, unlike for population-based data, RV allele-counting association methods will lead to inflated type I errors. However type I errors can be properly controlled by obtaining p values empirically through haplotype permutation. The power of the RV-TDT methods was evaluated and compared to the analysis of case-control data with a number of genetic and disease models. The RV-TDT was also used to analyze exome data from 199 Simons Simplex Collection autism trios and an association was observed with variants in ABCA7. Given the problem of adequately controlling for population substructure and admixture in RV association studies and the growing number of sequence-based trio studies, the RV-TDT is extremely beneficial to elucidate the involvement of RVs in the etiology of complex traits.
Keywords: Alleles; Autistic Disorder; Computer Simulation; Exome; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Haplotypes; Humans; Linkage Disequilibrium; Models, Genetic; Phenotype; Sequence Analysis, DNA

Recurrent activating mutation in PRKACA in cortisol-producing adrenal tumors. - Goh, Gerald; Scholl, Ute I; Healy, James M; Choi, Murim; Prasad, Manju L; Nelson-Williams, Carol; Kunstman, John W; Kuntsman, John W; Korah, Reju; Suttorp, Anna-Carinna; Dietrich, Dimo; Haase, Matthias; et al. (Nat Genet, 2014)
Adrenal tumors autonomously producing cortisol cause Cushing's syndrome. We performed exome sequencing of 25 tumor-normal pairs and identified 2 subgroups. Eight tumors (including three carcinomas) had many somatic copy number variants (CNVs) with frequent deletion of CDC42 and CDKN2A, amplification of 5q31.2 and protein-altering mutations in TP53 and RB1. Seventeen tumors (all adenomas) had no somatic CNVs or TP53 or RB1 mutations. Six of these had known gain-of-function mutations in CTNNB1 (β-catenin) or GNAS (Gαs). Six others had somatic mutations in PRKACA (protein kinase A (PKA) catalytic subunit) resulting in a p.Leu206Arg substitution. Further sequencing identified this mutation in 13 of 63 tumors (35% of adenomas with overt Cushing's syndrome). PRKACA, GNAS and CTNNB1 mutations were mutually exclusive. Leu206 directly interacts with the regulatory subunit of PKA, PRKAR1A. Leu206Arg PRKACA loses PRKAR1A binding, increasing the phosphorylation of downstream targets. PKA activity induces cortisol production and cell proliferation, providing a mechanism for tumor development. These findings define distinct mechanisms underlying adrenal cortisol-producing tumors.
Keywords: Adolescent; Adrenal Gland Neoplasms; Adult; Aged; Amino Acid Sequence; Base Sequence; cdc42 GTP-Binding Protein; Cell Proliferation; Cyclic AMP-Dependent Protein Kinase Catalytic Subunits; Cyclin-Dependent Kinase Inhibitor p16; DNA Copy Number Variations; Exome; Female; Gene Deletion; Gene Dosage; HEK293 Cells; Humans; Hydrocortisone; Male; Middle Aged; Molecular Sequence Data; Mutation; Phosphorylation; Sequence Analysis, DNA; Sequence Homology, Amino Acid

RNF213 rare variants in an ethnically diverse population with Moyamoya disease. - Cecchi, Alana C; Guo, Dongchuan; Ren, Zhao; Flynn, Kelly; Santos-Cortez, Regie Lyn P; Leal, Suzanne M; Wang, Gao T; Regalado, Ellen S; Steinberg, Gary K; Shendure, Jay; Bamshad, Michael J; Grotta, James C; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Moyamoya disease (MMD) is a rare, genetically heterogeneous cerebrovascular disease resulting from occlusion of the distal internal carotid arteries. A variant in the Ring Finger 213 gene (RNF213), altering arginine at position 4810 (p.R4810K), is associated with MMD in Asian populations. However, there are a lack of data on the role of RNF213 in patients with MMD of additional ethnicities and diasporic Asian populations. We investigate the contribution of RNF213 alterations to MMD in an ethnically diverse population based in the United States. METHODS: We initially sequenced RNF213 exons 43, 44, and 45 (encoding the eponymous RING finger domain) and exon 60 (encoding p.R4810K) in 86 ethnically diverse patients with MMD. Comprehensive exome sequencing data from 24 additional patients with MMD was then analyzed to identify RNF213 variants globally. Segregation of variants with MMD and other vascular diseases was assessed in families. RESULTS: RNF213 p.R4810K was identified in 56% (9/16) of patients with MMD of Asian descent and not in 94 patients of non-Asian descent. 3.6% (4/110) of patients had variants in the exons encoding the RING finger domain. Seven additional variants were identified in 29% (7/24) of patients with MMD who underwent exome sequencing. Segregation analysis supported an association with MMD for 2 variants and a lack of association with disease for 1 variant. CONCLUSIONS: These results confirm that alterations in RNF213 predispose patients of diverse ethnicities to MMD, and that the p.R4810K variant predisposes individuals of Asian descent in the United States to MMD.
Keywords: Adenosine Triphosphatases; Adolescent; Adult; Child; Cohort Studies; Ethnic Groups; Female; Genetic Variation; Humans; Male; Moyamoya Disease; Population Surveillance; Ubiquitin-Protein Ligases; Young Adult

Sclerocornea in a patient with van den Ende-Gupta syndrome homozygous for a SCARF2 microdeletion. - Migliavacca, Michele P; Sobreira, Nara L M; Antonialli, Graziela P M; Oliveira, Mariana M; Melaragno, Maria Isabel S A; Casteels, Ingele; de Ravel, Thomy; Brunoni, Decio; Valle, David; Perez, Ana Beatriz A (Am J Med Genet A, 2014)
Van den Ende-Gupta Syndrome (VDEGS) is an autosomal recessive disorder characterized by blepharophimosis, distinctive nose, hypoplastic maxilla, and skeletal abnormalities. Using homozygosity mapping in four VDEGS patients from three consanguineous families, Anastacio et al. [Anastacio et al. (2010); Am J Hum Genet 87:553-559] identified homozygous mutations in SCARF2, located at 22q11.2. Bedeschi et al. [2010] described a VDEGS patient with sclerocornea and cataracts with compound heterozygosity for the common 22q11.2 microdeletion and a hemizygous SCARF2 mutation. Because sclerocornea had been described in DiGeorge-velo-cardio-facial syndrome but not in VDEGS, they suggested that the ocular abnormalities were caused by the 22q11.2 microdeletion. We report on a 23-year-old male who presented with bilateral sclerocornea and the VDGEGS phenotype who was subsequently found to be homozygous for a 17 bp deletion in exon 4 of SCARF2. The occurrence of bilateral sclerocornea in our patient together with that of Bedeschi et al., suggests that the full VDEGS phenotype may include sclerocornea resulting from homozygosity or compound heterozygosity for loss of function variants in SCARF2.
Keywords: Abnormalities, Multiple; Adult; Arachnodactyly; Blepharophimosis; Bone and Bones; Chromosomes, Human, Pair 22; Contracture; Cornea; Corneal Diseases; Exons; Facies; Hand Deformities, Congenital; Homozygote; Humans; Male; Phenotype; Radiography; Scavenger Receptors, Class F; Sequence Analysis, DNA; Sequence Deletion; Young Adult

Solving glycosylation disorders: fundamental approaches reveal complicated pathways. - Freeze, Hudson H; Chong, Jessica X; Bamshad, Michael J; Ng, Bobby G (Am J Hum Genet, 2014)
Over 100 human genetic disorders result from mutations in glycosylation-related genes. In 2013, a new glycosylation disorder was reported every 17 days. This trend will probably continue given that at least 2% of the human genome encodes glycan-biosynthesis and -recognition proteins. Established biosynthetic pathways provide many candidate genes, but finding unanticipated mutated genes will offer new insights into glycosylation. Simple glycobiomarkers can be used in narrowing the candidates identified by exome and genome sequencing, and those can be validated by glycosylation analysis of serum or cells from affected individuals. Model organisms will expand the understanding of these mutations' impact on glycosylation and pathology. Here, we highlight some recently discovered glycosylation disorders and the barriers, breakthroughs, and surprises they presented. We predict that some glycosylation disorders might occur with greater frequency than current estimates of their prevalence. Moreover, the prevalence of some disorders differs substantially between European and African Americans.
Keywords: Congenital Disorders of Glycosylation; Exome; Genome, Human; Glucose; Glycogen; Glycosylation; Homeostasis; Humans; Mannose; Mutation

Somatic HRAS p.G12S mutation causes woolly hair and epidermal nevi. - Levinsohn, Jonathan L; Teng, Joyce; Craiglow, Brittany G; Loring, Erin C; Burrow, T Andrew; Mane, Shrikant S; Overton, John D; Lifton, Richard P; McNiff, Jennifer M; Lucky, Anne W; Choate, Keith A (J Invest Dermatol, 2014)
Keywords: Adherens Junctions; Child; Exome; Female; Genes, ras; Hair; Hair Diseases; Hair Follicle; Humans; Intermediate Filaments; Mosaicism; Mutation; Nevus; Phenotype; ras Proteins; Sequence Analysis, DNA; Signal Transduction

Somatic mutations in cerebral cortical malformations. - Morita, Hiroyuki; Komuro, Issei (N Engl J Med, 2014)
Keywords: Cerebral Cortex; DNA Mutational Analysis; Humans; Malformations of Cortical Development; Mutation

Somatic mutations in cerebral cortical malformations. - Jamuar, Saumya S; Lam, Anh-Thu N; Kircher, Martin; D'Gama, Alissa M; Wang, Jian; Barry, Brenda J; Zhang, Xiaochang; Hill, Robert Sean; Partlow, Jennifer N; Rozzo, Aldo; Servattalab, Sarah; Mehta, Bhaven K; et al. (N Engl J Med, 2014)
BACKGROUND: Although there is increasing recognition of the role of somatic mutations in genetic disorders, the prevalence of somatic mutations in neurodevelopmental disease and the optimal techniques to detect somatic mosaicism have not been systematically evaluated. METHODS: Using a customized panel of known and candidate genes associated with brain malformations, we applied targeted high-coverage sequencing (depth, ≥200×) to leukocyte-derived DNA samples from 158 persons with brain malformations, including the double-cortex syndrome (subcortical band heterotopia, 30 persons), polymicrogyria with megalencephaly (20), periventricular nodular heterotopia (61), and pachygyria (47). We validated candidate mutations with the use of Sanger sequencing and, for variants present at unequal read depths, subcloning followed by colony sequencing. RESULTS: Validated, causal mutations were found in 27 persons (17%; range, 10 to 30% for each phenotype). Mutations were somatic in 8 of the 27 (30%), predominantly in persons with the double-cortex syndrome (in whom we found mutations in DCX and LIS1), persons with periventricular nodular heterotopia (FLNA), and persons with pachygyria (TUBB2B). Of the somatic mutations we detected, 5 (63%) were undetectable with the use of traditional Sanger sequencing but were validated through subcloning and subsequent sequencing of the subcloned DNA. We found potentially causal mutations in the candidate genes DYNC1H1, KIF5C, and other kinesin genes in persons with pachygyria. CONCLUSIONS: Targeted sequencing was found to be useful for detecting somatic mutations in patients with brain malformations. High-coverage sequencing panels provide an important complement to whole-exome and whole-genome sequencing in the evaluation of somatic mutations in neuropsychiatric disease. (Funded by the National Institute of Neurological Disorders and Stroke and others.).
Keywords: Cerebral Cortex; Classical Lissencephalies and Subcortical Band Heterotopias; DNA Mutational Analysis; Humans; Lissencephaly; Magnetic Resonance Imaging; Malformations of Cortical Development; Mutation; Periventricular Nodular Heterotopia

Structural variation and missense mutation in SBDS associated with Shwachman-Diamond syndrome. - Carvalho, Claudia M B; Zuccherato, Luciana W; Williams, Christopher L; Neill, Nicholas J; Murdock, David R; Bainbridge, Matthew; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Ip, Wan; Guillerman, Robert Paul; Lupski, James R; et al. (BMC Med Genet, 2014)
BACKGROUND: Shwachman-Diamond syndrome (SDS) is an autosomal recessive ribosomopathy caused mainly by compound heterozygous mutations in SBDS. Structural variation (SV) involving the SBDS locus has been rarely reported in association with the disease. We aimed to determine whether an SV contributed to the pathogenesis of a case lacking biallelic SBDS point mutations. CASE PRESENTATION: Whole exome sequencing was performed in a patient with SDS lacking biallelic SBDS point mutations. Array comparative genomic hybridization and Southern blotting were used to seek SVs across the SBDS locus. Locus-specific polymerase chain reaction (PCR) encompassing flanking intronic sequence was also performed to investigate mutation within the locus. RNA expression and Western blotting were performed to analyze allele and protein expression. We found the child harbored a single missense mutation in SBDS (c.98A > C; p.K33T), inherited from the mother, and an SV in the SBDS locus, inherited from the father. The missense allele and SV segregated in accordance with Mendelian expectations for autosomal recessive SDS. Complementary DNA and western blotting analysis and locus specific PCR support the contention that the SV perturbed SBDS protein expression in the father and child. CONCLUSION: Our findings implicate genomic rearrangements in the pathogenesis of some cases of SDS and support patients lacking biallelic SBDS point mutations be tested for SV within the SBDS locus.
Keywords: Abdomen; Alleles; Bone Marrow Diseases; Cell Line, Transformed; Child, Preschool; Comparative Genomic Hybridization; DNA Mutational Analysis; Exocrine Pancreatic Insufficiency; Female; Gene Order; Humans; Lipomatosis; Mutagenesis, Insertional; Mutation; Mutation, Missense; Pedigree; Proteins; Radiography, Abdominal; Ultrasonography

TCIRG1-associated congenital neutropenia. - Makaryan, Vahagn; Rosenthal, Elisabeth A; Bolyard, Audrey Anna; Kelley, Merideth L; Below, Jennifer E; Bamshad, Michael J; Bofferding, Kathryn M; Smith, Joshua D; Buckingham, Kati; Boxer, Laurence A; Skokowa, Julia; Welte, Karl; et al. (Hum Mutat, 2014)
Severe congenital neutropenia (SCN) is a rare hematopoietic disorder, with estimated incidence of 1 in 200,000 individuals of European descent, many cases of which are inherited in an autosomal dominant pattern. Despite the fact that several causal genes have been identified, the genetic basis for >30% of cases remains unknown. We report a five-generation family segregating a novel single nucleotide variant (SNV) in TCIRG1. There is perfect cosegregation of the SNV with congenital neutropenia in this family; all 11 affected, but none of the unaffected, individuals carry this novel SNV. Western blot analysis show reduced levels of TCIRG1 protein in affected individuals, compared to healthy controls. Two unrelated patients with SCN, identified by independent investigators, are heterozygous for different, rare, highly conserved, coding variants in TCIRG1.
Keywords: DNA Mutational Analysis; Heterozygote; Humans; Mutation; Neutropenia; Pedigree; Vacuolar Proton-Translocating ATPases

Vaccine-associated varicella and rubella infections in severe combined immunodeficiency with isolated CD4 lymphocytopenia and mutations in IL7R detected by tandem whole exome sequencing and chromosomal microarray. - Bayer, D K; Martinez, C A; Sorte, H S; Forbes, L R; Demmler-Harrison, G J; Hanson, I C; Pearson, N M; Noroski, L M; Zaki, S R; Bellini, W J; Leduc, M S; Yang, Y; et al. (Clin Exp Immunol, 2014)
In areas without newborn screening for severe combined immunodeficiency (SCID), disease-defining infections may lead to diagnosis, and in some cases, may not be identified prior to the first year of life. We describe a female infant who presented with disseminated vaccine-acquired varicella (VZV) and vaccine-acquired rubella infections at 13 months of age. Immunological evaluations demonstrated neutropenia, isolated CD4 lymphocytopenia, the presence of CD8(+) T cells, poor lymphocyte proliferation, hypergammaglobulinaemia and poor specific antibody production to VZV infection and routine immunizations. A combination of whole exome sequencing and custom-designed chromosomal microarray with exon coverage of primary immunodeficiency genes detected compound heterozygous mutations (one single nucleotide variant and one intragenic copy number variant involving one exon) within the IL7R gene. Mosaicism for wild-type allele (20-30%) was detected in pretransplant blood and buccal DNA and maternal engraftment (5-10%) demonstrated in pretransplant blood DNA. This may be responsible for the patient's unusual immunological phenotype compared to classical interleukin (IL)-7Rα deficiency. Disseminated VZV was controlled with anti-viral and immune-based therapy, and umbilical cord blood stem cell transplantation was successful. Retrospectively performed T cell receptor excision circle (TREC) analyses completed on neonatal Guthrie cards identified absent TREC. This case emphasizes the danger of live viral vaccination in severe combined immunodeficiency (SCID) patients and the importance of newborn screening to identify patients prior to high-risk exposures. It also illustrates the value of aggressive pathogen identification and treatment, the influence newborn screening can have on morbidity and mortality and the significant impact of newer genomic diagnostic tools in identifying the underlying genetic aetiology for SCID patients.
Keywords: CD4-Positive T-Lymphocytes; Chickenpox; DNA Copy Number Variations; Exome; Female; Humans; Infant; Lymphopenia; Mutation; Oligonucleotide Array Sequence Analysis; Receptors, Interleukin-7; Rubella; Severe Combined Immunodeficiency; Vaccination

Variant association tools for quality control and analysis of large-scale sequence and genotyping array data. - Wang, Gao T; Peng, Bo; Leal, Suzanne M (Am J Hum Genet, 2014)
Currently there is great interest in detecting associations between complex traits and rare variants. In this report, we describe Variant Association Tools (VAT) and the VAT pipeline, which implements best practices for rare-variant association studies. Highlights of VAT include variant-site and call-level quality control (QC), summary statistics, phenotype- and genotype-based sample selection, variant annotation, selection of variants for association analysis, and a collection of rare-variant association methods for analyzing qualitative and quantitative traits. The association testing framework for VAT is regression based, which readily allows for flexible construction of association models with multiple covariates and weighting themes based on allele frequencies or predicted functionality. Additionally, pathway analyses, conditional analyses, and analyses of gene-gene and gene-environment interactions can be performed. VAT is capable of rapidly scanning through data by using multi-process computation, adaptive permutation, and simultaneously conducting association analysis via multiple methods. Results are available in text or graphic file formats and additionally can be output to relational databases for further annotation and filtering. An interface to R language also facilitates user implementation of novel association methods. The VAT's data QC and association-analysis pipeline can be applied to sequence, imputed, and genotyping array, e.g., "exome chip," data, providing a reliable and reproducible computational environment in which to analyze small- to large-scale studies with data from the latest genotyping and sequencing technologies. Application of the VAT pipeline is demonstrated through analysis of data from the 1000 Genomes project.
Keywords: Genetic Association Studies; Genetic Variation; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Multifactorial Inheritance; Quality Control; Software

Whole exome sequencing identifies de novo mutations in GATA6 associated with congenital diaphragmatic hernia. - Yu, Lan; Bennett, James T; Wynn, Julia; Carvill, Gemma L; Cheung, Yee Him; Shen, Yufeng; Mychaliska, George B; Azarow, Kenneth S; Crombleholme, Timothy M; Chung, Dai H; Potoka, Douglas; Warner, Brad W; et al. (J Med Genet, 2014)
BACKGROUND: Congenital diaphragmatic hernia (CDH) is a common birth defect affecting 1 in 3000 births. It is characterised by herniation of abdominal viscera through an incompletely formed diaphragm. Although chromosomal anomalies and mutations in several genes have been implicated, the cause for most patients is unknown. METHODS: We used whole exome sequencing in two families with CDH and congenital heart disease, and identified mutations in GATA6 in both. RESULTS: In the first family, we identified a de novo missense mutation (c.1366C>T, p.R456C) in a sporadic CDH patient with tetralogy of Fallot. In the second, a nonsense mutation (c.712G>T, p.G238*) was identified in two siblings with CDH and a large ventricular septal defect. The G238* mutation was inherited from their mother, who was clinically affected with congenital absence of the pericardium, patent ductus arteriosus and intestinal malrotation. Deep sequencing of blood and saliva-derived DNA from the mother suggested somatic mosaicism as an explanation for her milder phenotype, with only approximately 15% mutant alleles. To determine the frequency of GATA6 mutations in CDH, we sequenced the gene in 378 patients with CDH. We identified one additional de novo mutation (c.1071delG, p.V358Cfs34*). CONCLUSIONS: Mutations in GATA6 have been previously associated with pancreatic agenesis and congenital heart disease. We conclude that, in addition to the heart and the pancreas, GATA6 is involved in development of two additional organs, the diaphragm and the pericardium. In addition, we have shown that de novo mutations can contribute to the development of CDH, a common birth defect.
Keywords: Amino Acid Sequence; DNA Mutational Analysis; Exome; Female; GATA6 Transcription Factor; Hernia, Diaphragmatic; Hernias, Diaphragmatic, Congenital; Humans; Male; Molecular Sequence Data; Mutation; Sequence Alignment; Sequence Analysis, DNA

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome. - Bayram, Yavuz; Pehlivan, Davut; Karaca, Ender; Gambin, Tomasz; Jhangiani, Shalini N; Erdin, Serkan; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; Muzny, Donna; Elcioglu, Nursel H; Yildirim, M Selman; Bozkurt, Banu; et al. (Am J Med Genet A, 2014)
GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 were reported to cause GAPO syndrome. In our study we performed whole exome sequencing (WES) for five affected individuals from three Turkish kindreds segregating the GAPO trait. Exome sequencing analysis identified three novel homozygous mutations including; one frame-shift (c.1220_1221insT; p.Ala408Cysfs*2), one splice site (c.411A>G; p.Gln137Gln), and one non-synonymous (c.1150G>A; p.Gly384Ser) mutation in the ANTXR1 gene. Our studies expand the allelic spectrum in this rare condition and potentially provide insight into the role of ANTXR1 in the regulation of the extracellular matrix.
Keywords: Adolescent; Adult; Alopecia; Anodontia; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Facies; Family; Female; Growth Disorders; Humans; Male; Molecular Sequence Data; Mutation; Neoplasm Proteins; Optic Atrophies, Hereditary; Pedigree; Protein Structure, Tertiary; Receptors, Cell Surface

Whole-exome sequencing links TMCO1 defect syndrome with cerebro-facio-thoracic dysplasia. - Pehlivan, Davut; Karaca, Ender; Aydin, Hatip; Beck, Christine R; Gambin, Tomasz; Muzny, Donna M; Bilge Geckinli, B; Karaman, Ali; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Eur J Hum Genet, 2014)
Whole-exome sequencing (WES) is a type of disruptive technology that has tremendous influence on human and clinical genetics research. An efficient and cost-effective method, WES is now widely used as a diagnostic tool for identifying the molecular basis of genetic syndromes that are often challenging to diagnose. Here we report a patient with a clinical diagnosis of cerebro-facio-thoracic dysplasia (CFTD; MIM#213980) in whom we identified a homozygous splice-site mutation in the transmembrane and coiled-coil domains 1 (TMCO1) gene using WES. TMCO1 mutations cause craniofacial dysmorphism, skeletal anomalies characterized by multiple malformations of the vertebrae and ribs, and intellectual disability (MIM#614132). A retrospective review revealed that clinical manifestations of both syndromes are very similar and overlap remarkably. We propose that mutations of TMCO1 are not only responsible for craniofacial dysmorphism, skeletal anomalies and mental retardation syndrome but also for CFTD.
Keywords: Abnormalities, Multiple; Exome; Humans; Infant; Intellectual Disability; Male; Membrane Proteins; Mutation; Protein Isoforms

Whole-exome sequencing reveals GPIHBP1 mutations in infantile colitis with severe hypertriglyceridemia. - Gonzaga-Jauregui, Claudia; Mir, Sabina; Penney, Samantha; Jhangiani, Shalini; Midgen, Craig; Finegold, Milton; Muzny, Donna M; Wang, Min; Bacino, Carlos A; Gibbs, Richard A; Lupski, James R; Kellermayer, Richard; et al. (J Pediatr Gastroenterol Nutr, 2014)
Severe congenital hypertriglyceridemia (HTG) is a rare disorder caused by mutations in genes affecting lipoprotein lipase (LPL) activity. Here we report a 5-week-old Hispanic girl with severe HTG (12,031 mg/dL, normal limit 150 mg/dL) who presented with the unusual combination of lower gastrointestinal bleeding and milky plasma. Initial colonoscopy was consistent with colitis, which resolved with reduction of triglycerides. After negative sequencing of the LPL gene, whole-exome sequencing revealed novel compound heterozygous mutations in GPIHBP1. Our study broadens the phenotype of GPIHBP1-associated HTG, reinforces the effectiveness of whole-exome sequencing in Mendelian diagnoses, and implicates triglycerides in gastrointestinal mucosal injury.
Keywords: Colitis; DNA Mutational Analysis; Exome; Female; Humans; Hypertriglyceridemia; Infant; Receptors, Lipoprotein

ADCK4 mutations promote steroid-resistant nephrotic syndrome through CoQ10 biosynthesis disruption. - Ashraf, Shazia; Gee, Heon Yung; Woerner, Stephanie; Xie, Letian X; Vega-Warner, Virginia; Lovric, Svjetlana; Fang, Humphrey; Song, Xuewen; Cattran, Daniel C; Avila-Casado, Carmen; Paterson, Andrew D; Nitschké, Patrick; et al. (J Clin Invest, 2013)
Identification of single-gene causes of steroid-resistant nephrotic syndrome (SRNS) has furthered the understanding of the pathogenesis of this disease. Here, using a combination of homozygosity mapping and whole human exome resequencing, we identified mutations in the aarF domain containing kinase 4 (ADCK4) gene in 15 individuals with SRNS from 8 unrelated families. ADCK4 was highly similar to ADCK3, which has been shown to participate in coenzyme Q10 (CoQ10) biosynthesis. Mutations in ADCK4 resulted in reduced CoQ10 levels and reduced mitochondrial respiratory enzyme activity in cells isolated from individuals with SRNS and transformed lymphoblasts. Knockdown of adck4 in zebrafish and Drosophila recapitulated nephrotic syndrome-associated phenotypes. Furthermore, ADCK4 was expressed in glomerular podocytes and partially localized to podocyte mitochondria and foot processes in rat kidneys and cultured human podocytes. In human podocytes, ADCK4 interacted with members of the CoQ10 biosynthesis pathway, including COQ6, which has been linked with SRNS and COQ7. Knockdown of ADCK4 in podocytes resulted in decreased migration, which was reversed by CoQ10 addition. Interestingly, a patient with SRNS with a homozygous ADCK4 frameshift mutation had partial remission following CoQ10 treatment. These data indicate that individuals with SRNS with mutations in ADCK4 or other genes that participate in CoQ10 biosynthesis may be treatable with CoQ10.
Keywords: Adolescent; Adrenal Cortex Hormones; Amino Acid Sequence; Animals; Cells, Cultured; Child; Consanguinity; Conserved Sequence; Disease Models, Animal; DNA Mutational Analysis; Drosophila Proteins; Drug Resistance; Exome; Fibroblasts; Gene Knockdown Techniques; Humans; Mitochondria; Molecular Sequence Data; Mutation; Nephrotic Syndrome; Podocytes; Protein Kinases; Rats; Sequence Alignment; Sequence Homology, Amino Acid; Ubiquinone; Young Adult; Zebrafish; Zebrafish Proteins

ARMC4 mutations cause primary ciliary dyskinesia with randomization of left/right body asymmetry. - Hjeij, Rim; Lindstrand, Anna; Francis, Richard; Zariwala, Maimoona A; Liu, Xiaoqin; Li, You; Damerla, Rama; Dougherty, Gerard W; Abouhamed, Marouan; Olbrich, Heike; Loges, Niki T; Pennekamp, Petra; et al. (Am J Hum Genet, 2013)
The motive forces for ciliary movement are generated by large multiprotein complexes referred to as outer dynein arms (ODAs), which are preassembled in the cytoplasm prior to transport to the ciliary axonemal compartment. In humans, defects in structural components, docking complexes, or cytoplasmic assembly factors can cause primary ciliary dyskinesia (PCD), a disorder characterized by chronic airway disease and defects in laterality. By using combined high resolution copy-number variant and mutation analysis, we identified ARMC4 mutations in twelve PCD individuals whose cells showed reduced numbers of ODAs and severely impaired ciliary beating. Transient suppression in zebrafish and analysis of an ENU mouse mutant confirmed in both model organisms that ARMC4 is critical for left-right patterning. We demonstrate that ARMC4 is an axonemal protein that is necessary for proper targeting and anchoring of ODAs.
Keywords: Amino Acid Sequence; Animals; Armadillo Domain Proteins; Axoneme; Body Patterning; Cilia; DNA Copy Number Variations; DNA Mutational Analysis; Dyneins; Gene Expression Regulation; Humans; Kartagener Syndrome; Mice; Microtubule-Associated Proteins; Molecular Sequence Data; Mutation; Respiratory System; Zebrafish

Attitudes of African Americans toward return of results from exome and whole genome sequencing. - Yu, Joon-Ho; Crouch, Julia; Jamal, Seema M; Tabor, Holly K; Bamshad, Michael J (Am J Med Genet A, 2013)
Exome sequencing and whole genome sequencing (ES/WGS) present patients and research participants with the opportunity to benefit from a broad scope of genetic results of clinical and personal utility. Yet, this potential for benefit also risks disenfranchising populations such as African Americans (AAs) that are already underrepresented in genetic research and utilize genetic tests at lower rates than other populations. Understanding a diverse range of perspectives on consenting for ES/WGS and receiving ES/WGS results is necessary to ensure parity in genomic health care and research. We conducted a series of 13 focus groups (n = 76) to investigate if and how attitudes toward participation in ES/WGS research and return of results from ES/WGS differ between self-described AAs and non-AAs. The majority of both AAs and non-AAs were willing to participate in WGS studies and receive individual genetic results, but the fraction not interested in either was higher in AAs. This is due in part to different expectations of health benefits from ES/WGS and how results should be managed. Our results underscore the need to develop and test culturally tailored strategies for returning ES/WGS results to AAs.
Keywords: Adult; African Americans; Aged; Attitude; Exome; Female; Focus Groups; Genetic Research; Genome-Wide Association Study; Humans; Male; Middle Aged; Sequence Analysis, DNA; Surveys and Questionnaires; Washington

De novo mutations in histone-modifying genes in congenital heart disease. - Zaidi, Samir; Choi, Murim; Wakimoto, Hiroko; Ma, Lijiang; Jiang, Jianming; Overton, John D; Romano-Adesman, Angela; Bjornson, Robert D; Breitbart, Roger E; Brown, Kerry K; Carriero, Nicholas J; Cheung, Yee Him; et al. (Nature, 2013)
Congenital heart disease (CHD) is the most frequent birth defect, affecting 0.8% of live births. Many cases occur sporadically and impair reproductive fitness, suggesting a role for de novo mutations. Here we compare the incidence of de novo mutations in 362 severe CHD cases and 264 controls by analysing exome sequencing of parent-offspring trios. CHD cases show a significant excess of protein-altering de novo mutations in genes expressed in the developing heart, with an odds ratio of 7.5 for damaging (premature termination, frameshift, splice site) mutations. Similar odds ratios are seen across the main classes of severe CHD. We find a marked excess of de novo mutations in genes involved in the production, removal or reading of histone 3 lysine 4 (H3K4) methylation, or ubiquitination of H2BK120, which is required for H3K4 methylation. There are also two de novo mutations in SMAD2, which regulates H3K27 methylation in the embryonic left-right organizer. The combination of both activating (H3K4 methylation) and inactivating (H3K27 methylation) chromatin marks characterizes 'poised' promoters and enhancers, which regulate expression of key developmental genes. These findings implicate de novo point mutations in several hundreds of genes that collectively contribute to approximately 10% of severe CHD.
Keywords: Adult; Case-Control Studies; Child; Chromatin; DNA Mutational Analysis; Enhancer Elements, Genetic; Exome; Female; Genes, Developmental; Heart Diseases; Histones; Humans; Lysine; Male; Methylation; Mutation; Odds Ratio; Promoter Regions, Genetic

Deletions of recessive disease genes: CNV contribution to carrier states and disease-causing alleles. - Boone, Philip M; Campbell, Ian M; Baggett, Brett C; Soens, Zachry T; Rao, Mitchell M; Hixson, Patricia M; Patel, Ankita; Bi, Weimin; Cheung, Sau Wai; Lalani, Seema R; Beaudet, Arthur L; Stankiewicz, Pawel; et al. (Genome Res, 2013)
Over 1200 recessive disease genes have been described in humans. The prevalence, allelic architecture, and per-genome load of pathogenic alleles in these genes remain to be fully elucidated, as does the contribution of DNA copy-number variants (CNVs) to carrier status and recessive disease. We mined CNV data from 21,470 individuals obtained by array-comparative genomic hybridization in a clinical diagnostic setting to identify deletions encompassing or disrupting recessive disease genes. We identified 3212 heterozygous potential carrier deletions affecting 419 unique recessive disease genes. Deletion frequency of these genes ranged from one occurrence to 1.5%. When compared with recessive disease genes never deleted in our cohort, the 419 recessive disease genes affected by at least one carrier deletion were longer and located farther from known dominant disease genes, suggesting that the formation and/or prevalence of carrier CNVs may be affected by both local and adjacent genomic features and by selection. Some subjects had multiple carrier CNVs (307 subjects) and/or carrier deletions encompassing more than one recessive disease gene (206 deletions). Heterozygous deletions spanning multiple recessive disease genes may confer carrier status for multiple single-gene disorders, for complex syndromes resulting from the combination of two or more recessive conditions, or may potentially cause clinical phenotypes due to a multiply heterozygous state. In addition to carrier mutations, we identified homozygous and hemizygous deletions potentially causative for recessive disease. We provide further evidence that CNVs contribute to the allelic architecture of both carrier and recessive disease-causing mutations. Thus, a complete recessive carrier screening method or diagnostic test should detect CNV alleles.
Keywords: Alleles; Comparative Genomic Hybridization; Databases, Genetic; DNA Copy Number Variations; Gene Deletion; Gene Frequency; Genes, Dominant; Genes, Recessive; Genetic Diseases, Inborn; Homozygote; Humans

Effect of catechol-o-methyltransferase-gene (COMT) variants on experimental and acute postoperative pain in 1,000 women undergoing surgery for breast cancer. - Kambur, Oleg; Kaunisto, Mari A; Tikkanen, Emmi; Leal, Suzanne M; Ripatti, Samuli; Kalso, Eija A (Anesthesiology, 2013)
BACKGROUND: Catechol-O-methyltransferase (COMT) metabolizes catecholamines in different tissues. Polymorphisms in COMT gene can attenuate COMT activity and increase sensitivity to pain. Human studies exploring the effect of COMT polymorphisms on pain sensitivity have mostly included small, heterogeneous samples and have ignored several important single nucleotide polymorphisms (SNPs). This study examines the effect of COMT polymorphisms on experimental and postoperative pain phenotypes in a large ethnically homogeneous female patient cohort. METHODS: Intensity of cold (+2-4°C) and heat (+48°C) pain and tolerance to cold pain were assessed in 1,000 patients scheduled for breast cancer surgery. Acute postoperative pain and oxycodone requirements were recorded. Twenty-two COMT SNPs were genotyped and their association with six pain phenotypes analyzed with linear regression. RESULTS: There was no association between any of the tested pain phenotypes and SNP rs4680. The strongest association signals were seen between rs165774 and heat pain intensity as well as rs887200 and cold pain intensity. In both cases, minor allele carriers reported less pain. Neither of these results remained significant after strict multiple testing corrections. When analyzed further, the effect of rs887200 was, however, shown to be significant and consistent throughout the cold pressure test. No evidence of association between the SNPs and postoperative oxycodone consumption was found. CONCLUSIONS: SNPs rs887200 and rs165774 located in the untranslated regions of the gene had the strongest effects on pain sensitivity. Their effect on pain is described here for the first time. These results should be confirmed in further studies and the potential functional mechanisms of the variants studied.
Keywords: Acute Pain; Adult; Aged; Analgesics, Opioid; Anesthesia; Breast Neoplasms; Catechol O-Methyltransferase; Cold Temperature; Databases, Genetic; Female; Follow-Up Studies; Genetic Variation; Genome-Wide Association Study; Genotype; Haplotypes; Hot Temperature; Humans; Middle Aged; Oxycodone; Pain Measurement; Pain, Postoperative; Polymorphism, Single Nucleotide

Evidence for replicative mechanism in a CHD7 rearrangement in a patient with CHARGE syndrome. - Vatta, Matteo; Niu, Zhiyv; Lupski, James R; Putnam, Philip; Spoonamore, Katherine G; Fang, Ping; Eng, Christine M; Willis, Alecia S (Am J Med Genet A, 2013)
Haploinsufficiency of CHD7 (OMIM# 608892) is known to cause CHARGE syndrome (OMIM# 214800). Molecular testing supports a definitive diagnosis in approximately 65-70% of cases. Most CHD7 mutations arise de novo, and no mutations affecting exon-7 have been reported to date. We report on an 8-year-old girl diagnosed with CHARGE syndrome that was referred to our laboratory for comprehensive CHD7 gene screening. Genomic DNA from the subject with a suspected diagnosis of CHARGE was isolated from peripheral blood lymphocytes and comprehensive Sanger sequencing, along with deletion/duplication analysis of the CHD7 gene using multiplex ligation-dependent probe amplification (MLPA), was performed. MLPA analysis identified a reduced single probe signal for exon-7 of the CHD7 gene consistent with potential heterozygous deletion. Long-range PCR breakpoint analysis identified a complex genomic rearrangement (CGR) leading to the deletion of exon-7 and breakpoints consistent with a replicative mechanism such as fork stalling and template switching (FoSTeS) or microhomology-mediated break-induced replication (MMBIR). Taken together this represents the first evidence for a CHD7 intragenic CGR in a patient with CHARGE syndrome leading to what appears to be also the first report of a mutation specifically disrupting exon-7. Although likely rare, CGR may represent an overlooked mechanism in subjects with CHARGE syndrome that can be missed by current sequencing and dosage assays.
Keywords: Abnormalities, Multiple; CHARGE Syndrome; Child; DNA Helicases; DNA Replication; DNA-Binding Proteins; Exons; Female; Gene Deletion; Haploinsufficiency; Humans; Mutation

Exome sequencing resolves apparent incidental findings and reveals further complexity of SH3TC2 variant alleles causing Charcot-Marie-Tooth neuropathy. - Lupski, James R; Gonzaga-Jauregui, Claudia; Yang, Yaping; Bainbridge, Matthew N; Jhangiani, Shalini; Buhay, Christian J; Kovar, Christie L; Wang, Min; Hawes, Alicia C; Reid, Jeffrey G; Eng, Christine; Muzny, Donna M; et al. (Genome Med, 2013)
BACKGROUND: The debate regarding the relative merits of whole genome sequencing (WGS) versus exome sequencing (ES) centers around comparative cost, average depth of coverage for each interrogated base, and their relative efficiency in the identification of medically actionable variants from the myriad of variants identified by each approach. Nevertheless, few genomes have been subjected to both WGS and ES, using multiple next generation sequencing platforms. In addition, no personal genome has been so extensively analyzed using DNA derived from peripheral blood as opposed to DNA from transformed cell lines that may either accumulate mutations during propagation or clonally expand mosaic variants during cell transformation and propagation. METHODS: We investigated a genome that was studied previously by SOLiD chemistry using both ES and WGS, and now perform six independent ES assays (Illumina GAII (x2), Illumina HiSeq (x2), Life Technologies' Personal Genome Machine (PGM) and Proton), and one additional WGS (Illumina HiSeq). RESULTS: We compared the variants identified by the different methods and provide insights into the differences among variants identified between ES runs in the same technology platform and among different sequencing technologies. We resolved the true genotypes of medically actionable variants identified in the proband through orthogonal experimental approaches. Furthermore, ES identified an additional SH3TC2 variant (p.M1?) that likely contributes to the phenotype in the proband. CONCLUSIONS: ES identified additional medically actionable variant calls and helped resolve ambiguous single nucleotide variants (SNV) documenting the power of increased depth of coverage of the captured targeted regions. Comparative analyses of WGS and ES reveal that pseudogenes and segmental duplications may explain some instances of apparent disease mutations in unaffected individuals.

Incidental copy-number variants identified by routine genome testing in a clinical population. - Boone, Philip M; Soens, Zachry T; Campbell, Ian M; Stankiewicz, Pawel; Cheung, Sau Wai; Patel, Ankita; Beaudet, Arthur L; Plon, Sharon E; Shaw, Chad A; McGuire, Amy L; Lupski, James R (Genet Med, 2013)
PURPOSE: Mutational load of susceptibility variants has not been studied on a genomic scale in a clinical population, nor has the potential to identify these mutations as incidental findings during clinical testing been systematically ascertained. METHODS: Array comparative genomic hybridization, a method for genome-wide detection of DNA copy-number variants, was performed clinically on DNA from 9,005 individuals. Copy-number variants encompassing or disrupting single genes were identified and analyzed for their potential to confer predisposition to dominant, adult-onset disease. Multigene copy-number variants affecting dominant, adult-onset cancer syndrome genes were also assessed. RESULTS: In our cohort, 83 single-gene copy-number variants affected 40 unique genes associated with dominant, adult-onset disorders and unrelated to the patients' referring diagnoses (i.e., incidental) were found. Fourteen of these copy-number variants are likely disease-predisposing, 25 are likely benign, and 44 are of unknown clinical consequence. When incidental copy-number variants spanning up to 20 genes were considered, 27 copy-number variants affected 17 unique genes associated with dominant, adult-onset cancer predisposition. CONCLUSION: Copy-number variants potentially conferring susceptibility to adult-onset disease can be identified as incidental findings during routine genome-wide testing. Some of these mutations may be medically actionable, enabling disease surveillance or prevention; however, most incidentally observed single-gene copy-number variants are currently of unclear significance to the patient.
Keywords: Age of Onset; Base Sequence; Chromosome Mapping; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Order; Genetic Predisposition to Disease; Humans; Inheritance Patterns; Male; Reproducibility of Results

Macular telangiectasia type 2. - Charbel Issa, Peter; Gillies, Mark C; Chew, Emily Y; Bird, Alan C; Heeren, Tjebo F C; Peto, Tunde; Holz, Frank G; Scholl, Hendrik P N (Prog Retin Eye Res, 2013)
Macular telangiectasia type 2 is a bilateral disease of unknown cause with characteristic alterations of the macular capillary network and neurosensory atrophy. Its prevalence may be underestimated and has recently been shown to be as high as 0.1% in persons 40 years and older. Biomicroscopy may show reduced retinal transparency, crystalline deposits, mildly ectatic capillaries, blunted venules, retinal pigment plaques, foveal atrophy, and neovascular complexes. Fluorescein angiography shows telangiectatic capillaries predominantly temporal to the foveola in the early phase and a diffuse hyperfluorescence in the late phase. High-resolution optical coherence tomography (OCT) may reveal disruption of the photoreceptor inner segment-outer segment border, hyporeflective cavities at the level of the inner or outer retina, and atrophy of the retina in later stages. Macular telangiectasia type 2 shows a unique depletion of the macular pigment in the central retina and recent therapeutic trials showed that such depleted areas cannot re-accumulate lutein and zeaxanthin after oral supplementation. There have been various therapeutic approaches with limited or no efficacy. Recent clinical trials with compounds that block vascular endothelial growth factor (VEGF) have established the role of VEGF in the pathophysiology of the disease, but have not shown significant efficacy, at least for the non-neovascular disease stages. Recent progress in structure-function correlation may help to develop surrogate outcome measures for future clinical trials. In this review article, we summarize the current knowledge on macular telangiectasia type 2, including the epidemiology, the genetics, the clinical findings, the staging and the differential diagnosis of the disease. Findings using retinal imaging are discussed, including fluorescein angiography, OCT, adaptive optics imaging, confocal scanning laser ophthalmoscopy, and fundus autofluorescence, as are the findings using visual function testing including visual acuity and fundus-controlled microperimetry. We provide an overview of the therapeutic approaches for both non-neovascular and neovascular disease stages and provide a perspective of future directions including animal models and potential therapeutic approaches.
Keywords: Diagnosis, Differential; Humans; Macula Lutea; Retinal Diseases; Telangiectasis; Visual Acuity

Mosaicism of the UDP-galactose transporter SLC35A2 causes a congenital disorder of glycosylation. - Ng, Bobby G; Buckingham, Kati J; Raymond, Kimiyo; Kircher, Martin; Turner, Emily H; He, Miao; Smith, Joshua D; Eroshkin, Alexey; Szybowska, Marta; Losfeld, Marie E; Chong, Jessica X; Kozenko, Mariya; et al. (Am J Hum Genet, 2013)
Biochemical analysis and whole-exome sequencing identified mutations in the Golgi-localized UDP-galactose transporter SLC35A2 that define an undiagnosed X-linked congenital disorder of glycosylation (CDG) in three unrelated families. Each mutation reduced UDP-galactose transport, leading to galactose-deficient glycoproteins. Two affected males were somatic mosaics, suggesting that a wild-type SLC35A2 allele may be required for survival. In infancy, the commonly used biomarker transferrin showed abnormal glycosylation, but its appearance became normal later in childhood, without any corresponding clinical improvement. This may indicate selection against cells carrying the mutant allele. To detect other individuals with such mutations, we suggest transferrin testing in infancy. Here, we report somatic mosaicism in CDG, and our work stresses the importance of combining both genetic and biochemical diagnoses.
Keywords: Biological Transport; Case-Control Studies; Child; Child, Preschool; Congenital Disorders of Glycosylation; Exome; Female; Glycosylation; Humans; Male; Monosaccharide Transport Proteins; Mosaicism; Mutation; Spectrometry, Mass, Electrospray Ionization; Transferrin; Uridine Diphosphate Galactose

Mutations in DSTYK and dominant urinary tract malformations. - Sanna-Cherchi, Simone; Sampogna, Rosemary V; Papeta, Natalia; Burgess, Katelyn E; Nees, Shannon N; Perry, Brittany J; Choi, Murim; Bodria, Monica; Liu, Yan; Weng, Patricia L; Lozanovski, Vladimir J; Verbitsky, Miguel; et al. (N Engl J Med, 2013)
BACKGROUND: Congenital abnormalities of the kidney and the urinary tract are the most common cause of pediatric kidney failure. These disorders are highly heterogeneous, and the etiologic factors are poorly understood. METHODS: We performed genomewide linkage analysis and whole-exome sequencing in a family with an autosomal dominant form of congenital abnormalities of the kidney or urinary tract (seven affected family members). We also performed a sequence analysis in 311 unrelated patients, as well as histologic and functional studies. RESULTS: Linkage analysis identified five regions of the genome that were shared among all affected family members. Exome sequencing identified a single, rare, deleterious variant within these linkage intervals, a heterozygous splice-site mutation in the dual serine-threonine and tyrosine protein kinase gene (DSTYK). This variant, which resulted in aberrant splicing of messenger RNA, was present in all affected family members. Additional, independent DSTYK mutations, including nonsense and splice-site mutations, were detected in 7 of 311 unrelated patients. DSTYK is highly expressed in the maturing epithelia of all major organs, localizing to cell membranes. Knockdown in zebrafish resulted in developmental defects in multiple organs, which suggested loss of fibroblast growth factor (FGF) signaling. Consistent with this finding is the observation that DSTYK colocalizes with FGF receptors in the ureteric bud and metanephric mesenchyme. DSTYK knockdown in human embryonic kidney cells inhibited FGF-stimulated phosphorylation of extracellular-signal-regulated kinase (ERK), the principal signal downstream of receptor tyrosine kinases. CONCLUSIONS: We detected independent DSTYK mutations in 2.3% of patients with congenital abnormalities of the kidney or urinary tract, a finding that suggests that DSTYK is a major determinant of human urinary tract development, downstream of FGF signaling. (Funded by the National Institutes of Health and others.).
Keywords: Adult; Animals; Base Sequence; Child; Exome; Female; Gene Knockdown Techniques; Genetic Linkage; Genome-Wide Association Study; Heterozygote; Humans; Infant; Kidney; Male; Mice; Molecular Sequence Data; Mutation; Pedigree; Receptor-Interacting Protein Serine-Threonine Kinases; RNA, Small Interfering; Urinary Tract; Urogenital Abnormalities; Young Adult

Mutations in ECEL1 cause distal arthrogryposis type 5D. - McMillin, Margaret J; Below, Jennifer E; Shively, Kathryn M; Beck, Anita E; Gildersleeve, Heidi I; Pinner, Jason; Gogola, Gloria R; Hecht, Jacqueline T; Grange, Dorothy K; Harris, David J; Earl, Dawn L; Jagadeesh, Sujatha; et al. (Am J Hum Genet, 2013)
Distal arthrogryposis (DA) syndromes are the most common of the heritable congenital-contracture disorders, and ~50% of cases are caused by mutations in genes that encode contractile proteins of skeletal myofibers. DA type 5D (DA5D) is a rare, autosomal-recessive DA previously defined by us and is characterized by congenital contractures of the hands and feet, along with distinctive facial features, including ptosis. We used linkage analysis and whole-genome sequencing of a multiplex consanguineous family to identify in endothelin-converting enzyme-like 1 (ECEL1) mutations that result in DA5D. Evaluation of a total of seven families affected by DA5D revealed in five families ECEL1 mutations that explain ~70% of cases overall. ECEL1 encodes a neuronal endopeptidase and is expressed in the brain and peripheral nerves. Mice deficient in Ecel1 exhibit perturbed terminal branching of motor neurons to the endplate of skeletal muscles, resulting in poor formation of the neuromuscular junction. Our results distinguish a second developmental pathway that causes congenital-contracture syndromes.
Keywords: Arthrogryposis; Consanguinity; Female; Genetic Linkage; Humans; Male; Metalloendopeptidases; Mutation; Sequence Analysis, DNA

Mutations in KARS, encoding lysyl-tRNA synthetase, cause autosomal-recessive nonsyndromic hearing impairment DFNB89. - Santos-Cortez, Regie Lyn P; Lee, Kwanghyuk; Azeem, Zahid; Antonellis, Patrick J; Pollock, Lana M; Khan, Saadullah; Andrade-Elizondo, Paula B; Chiu, Ilene; Adams, Mark D; Basit, Sulman; Smith, Joshua D; Nickerson, Deborah A; et al. (Am J Hum Genet, 2013)
Previously, DFNB89, a locus associated with autosomal-recessive nonsyndromic hearing impairment (ARNSHI), was mapped to chromosomal region 16q21-q23.2 in three unrelated, consanguineous Pakistani families. Through whole-exome sequencing of a hearing-impaired individual from each family, missense mutations were identified at highly conserved residues of lysyl-tRNA synthetase (KARS): the c.1129G>A (p.Asp377Asn) variant was found in one family, and the c.517T>C (p.Tyr173His) variant was found in the other two families. Both variants were predicted to be damaging by multiple bioinformatics tools. The two variants both segregated with the nonsyndromic-hearing-impairment phenotype within the three families, and neither mutation was identified in ethnically matched controls or within variant databases. Individuals homozygous for KARS mutations had symmetric, severe hearing impairment across all frequencies but did not show evidence of auditory or limb neuropathy. It has been demonstrated that KARS is expressed in hair cells of zebrafish, chickens, and mice. Moreover, KARS has strong localization to the spiral ligament region of the cochlea, as well as to Deiters' cells, the sulcus epithelium, the basilar membrane, and the surface of the spiral limbus. It is hypothesized that KARS variants affect aminoacylation in inner-ear cells by interfering with binding activity to tRNA or p38 and with tetramer formation. The identification of rare KARS variants in ARNSHI-affected families defines a gene that is associated with ARNSHI.
Keywords: Animals; Case-Control Studies; Chickens; Cochlea; Computational Biology; Consanguinity; Female; Genetic Linkage; Hair Cells, Auditory, Inner; Haplotypes; Hearing Loss; Homozygote; Humans; Lysine-tRNA Ligase; Male; Mice; Mutation, Missense; Pedigree; Transfer RNA Aminoacylation; Zebrafish

Mutations in KCTD1 cause scalp-ear-nipple syndrome. - Marneros, Alexander G; Beck, Anita E; Turner, Emily H; McMillin, Margaret J; Edwards, Matthew J; Field, Michael; de Macena Sobreira, Nara Lygia; Perez, Ana Beatriz A; Fortes, Jose A R; Lampe, Anne K; Giovannucci Uzielli, Maria Luisa; Gordon, Christopher T; et al. (Am J Hum Genet, 2013)
Scalp-ear-nipple (SEN) syndrome is a rare, autosomal-dominant disorder characterized by cutis aplasia of the scalp; minor anomalies of the external ears, digits, and nails; and malformations of the breast. We used linkage analysis and exome sequencing of a multiplex family affected by SEN syndrome to identify potassium-channel tetramerization-domain-containing 1 (KCTD1) mutations that cause SEN syndrome. Evaluation of a total of ten families affected by SEN syndrome revealed KCTD1 missense mutations in each family tested. All of the mutations occurred in a KCTD1 region encoding a highly conserved bric-a-brac, tram track, and broad complex (BTB) domain that is required for transcriptional repressor activity. KCTD1 inhibits the transactivation of the transcription factor AP-2α (TFAP2A) via its BTB domain, and mutations in TFAP2A cause cutis aplasia in individuals with branchiooculofacial syndrome (BOFS), suggesting a potential overlap in the pathogenesis of SEN syndrome and BOFS. The identification of KCTD1 mutations in SEN syndrome reveals a role for this BTB-domain-containing transcriptional repressor during ectodermal development.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Branchio-Oto-Renal Syndrome; Ear, External; Ectodermal Dysplasia; Exome; Female; Humans; Hypospadias; Male; Molecular Sequence Data; Muscle Hypotonia; Mutation, Missense; Nipples; Pedigree; Phenotype; Protein Structure, Tertiary; Repressor Proteins; Scalp; Sequence Homology, Amino Acid

Mutations in LAMB1 cause cobblestone brain malformation without muscular or ocular abnormalities. - Radmanesh, Farid; Çağlayan, Ahmet Okay; Silhavy, Jennifer L; Yilmaz, Cahide; Cantagrel, Vincent; Omar, Tarek; Rosti, Basak; Kaymakçalan, Hande; Gabriel, Stacey; Li, Mingfeng; Šestan, Nenad; Bilguvar, Kaya; et al. (Am J Hum Genet, 2013)
Cobblestone brain malformation (COB) is a neuronal migration disorder characterized by protrusions of neurons beyond the first cortical layer at the pial surface of the brain. It is usually seen in association with dystroglycanopathy types of congenital muscular dystrophies (CMDs) and ocular abnormalities termed muscle-eye-brain disease. Here we report homozygous deleterious mutations in LAMB1, encoding laminin subunit beta-1, in two families with autosomal-recessive COB. Affected individuals displayed a constellation of brain malformations including cortical gyral and white-matter signal abnormalities, severe cerebellar dysplasia, brainstem hypoplasia, and occipital encephalocele, but they had less apparent ocular or muscular abnormalities than are typically observed in COB. LAMB1 is localized to the pial basement membrane, suggesting that defective connection between radial glial cells and the pial surface mediated by LAMB1 leads to this malformation.
Keywords: Basement Membrane; Brain; Cerebellum; Cerebral Cortex; Encephalocele; Female; Genetic Predisposition to Disease; Homozygote; Humans; Laminin; Male; Muscular Dystrophies; Nervous System Malformations; Neuroglia; Neurons; Sequence Deletion; Walker-Warburg Syndrome

Mutations in VRK1 associated with complex motor and sensory axonal neuropathy plus microcephaly. - Gonzaga-Jauregui, Claudia; Lotze, Timothy; Jamal, Leila; Penney, Samantha; Campbell, Ian M; Pehlivan, Davut; Hunter, Jill V; Woodbury, Suzanne L; Raymond, Gerald; Adesina, Adekunle M; Jhangiani, Shalini N; Reid, Jeffrey G; et al. (JAMA Neurol, 2013)
IMPORTANCE: Patients with rare diseases and complex clinical presentations represent a challenge for clinical diagnostics. Genomic approaches are allowing the identification of novel variants in genes for very rare disorders, enabling a molecular diagnosis. Genomics is also revealing a phenotypic expansion whereby the full spectrum of clinical expression conveyed by mutant alleles at a locus can be better appreciated. OBJECTIVE: To elucidate the molecular cause of a complex neuropathy phenotype in 3 patients by applying genomic sequencing strategies. DESIGN, SETTING, AND PARTICIPANTS: Three affected individuals from 2 unrelated families presented with a complex neuropathy phenotype characterized by axonal sensorimotor neuropathy and microcephaly. They were recruited into the Centers for Mendelian Genomics research program to identify the molecular cause of their phenotype. Whole-genome, targeted whole-exome sequencing, and high-resolution single-nucleotide polymorphism arrays were performed in genetics clinics of tertiary care pediatric hospitals and biomedical research institutions. MAIN OUTCOMES AND MEASURES: Whole-genome and whole-exome sequencing identified the variants responsible for the patients' clinical phenotype. RESULTS: We identified compound heterozygous alleles in 2 affected siblings from 1 family and a homozygous nonsense variant in the third unrelated patient in the vaccinia-related kinase 1 gene (VRK1). In the latter subject, we found a common haplotype on which the nonsense mutation occurred and that segregates in the Ashkenazi Jewish population. CONCLUSIONS AND RELEVANCE: We report the identification of disease-causing alleles in 3 children from 2 unrelated families with a previously uncharacterized complex axonal motor and sensory neuropathy accompanied by severe nonprogressive microcephaly and cerebral dysgenesis. Our data raise the question of whether VRK1 mutations disturb cell cycle progression and may result in apoptosis of cells in the nervous system. The application of unbiased genomic approaches allows the identification of potentially pathogenic mutations in unsuspected genes in highly genetically heterogeneous and uncharacterized neurological diseases.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Hereditary Sensory and Motor Neuropathy; Humans; Infant; Intracellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Microcephaly; Mutation; Neural Conduction; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases

Perrault syndrome is caused by recessive mutations in CLPP, encoding a mitochondrial ATP-dependent chambered protease. - Jenkinson, Emma M; Rehman, Atteeq U; Walsh, Tom; Clayton-Smith, Jill; Lee, Kwanghyuk; Morell, Robert J; Drummond, Meghan C; Khan, Shaheen N; Naeem, Muhammad Asif; Rauf, Bushra; Billington, Neil; Schultz, Julie M; et al. (Am J Hum Genet, 2013)
Perrault syndrome is a genetically and clinically heterogeneous autosomal-recessive condition characterized by sensorineural hearing loss and ovarian failure. By a combination of linkage analysis, homozygosity mapping, and exome sequencing in three families, we identified mutations in CLPP as the likely cause of this phenotype. In each family, affected individuals were homozygous for a different pathogenic CLPP allele: c.433A>C (p.Thr145Pro), c.440G>C (p.Cys147Ser), or an experimentally demonstrated splice-donor-site mutation, c.270+4A>G. CLPP, a component of a mitochondrial ATP-dependent proteolytic complex, is a highly conserved endopeptidase encoded by CLPP and forms an element of the evolutionarily ancient mitochondrial unfolded-protein response (UPR(mt)) stress signaling pathway. Crystal-structure modeling suggests that both substitutions would alter the structure of the CLPP barrel chamber that captures unfolded proteins and exposes them to proteolysis. Together with the previous identification of mutations in HARS2, encoding mitochondrial histidyl-tRNA synthetase, mutations in CLPP expose dysfunction of mitochondrial protein homeostasis as a cause of Perrault syndrome.
Keywords: Adenosine Triphosphate; Adolescent; Adult; ATP-Dependent Proteases; Endopeptidase Clp; Exome; Female; Genes, Recessive; Gonadal Dysgenesis, 46,XX; Hearing Loss, Sensorineural; Homozygote; Humans; In Situ Hybridization; Male; Mitochondria; Mutation; Pedigree; Phenotype; Young Adult

PhenoDB: a new web-based tool for the collection, storage, and analysis of phenotypic features. - Hamosh, Ada; Sobreira, Nara; Hoover-Fong, Julie; Sutton, V Reid; Boehm, Corinne; Schiettecatte, François; Valle, David (Hum Mutat, 2013)
To interpret whole exome/genome sequence data for clinical and research purposes, comprehensive phenotypic information, knowledge of pedigree structure, and results of previous clinical testing are essential. With these requirements in mind and to meet the needs of the Centers for Mendelian Genomics project, we have developed PhenoDB (http://phenodb.net), a secure, Web-based portal for entry, storage, and analysis of phenotypic and other clinical information. The phenotypic features are organized hierarchically according to the major headings and subheadings of the Online Mendelian Inheritance in Man (OMIM®) clinical synopses, with further subdivisions according to structure and function. Every string allows for a free-text entry. All of the approximately 2,900 features use the preferred term from Elements of Morphology and are fully searchable and mapped to the Human Phenotype Ontology and Elements of Morphology. The PhenoDB allows for ascertainment of relevant information from a case in a family or cohort, which is then searchable by family, OMIM number, phenotypic feature, mode of inheritance, genes screened, and so on. The database can also be used to format phenotypic data for submission to dbGaP for appropriately consented individuals. PhenoDB was built using Django, an open source Web development tool, and is freely available through the Johns Hopkins McKusick-Nathans Institute of Genetic Medicine (http://phenodb.net).
Keywords: Databases, Factual; Genomics; Humans; Internet; Medical Informatics; Phenotype; Software

Practices and policies of clinical exome sequencing providers: analysis and implications. - Jamal, Seema M; Yu, Joon-Ho; Chong, Jessica X; Dent, Karin M; Conta, Jessie H; Tabor, Holly K; Bamshad, Michael J (Am J Med Genet A, 2013)
Exome and whole genome sequencing (ES/WGS) offer potential advantages over traditional approaches to diagnostic genetic testing. Consequently, use of ES/WGS in clinical settings is rapidly becoming commonplace. Yet there are myriad moral, ethical, and perhaps legal implications attached to the use of ES and health care professionals and institutions will need to consider these implications in the context of the varied practices and policies of ES service providers. We developed "core elements" of content and procedures for informed consent, data sharing, and results management and a quantitative scale to assess the extent to which research protocols met the standards established by these core elements. We then used these tools to evaluate the practices and policies of each of the 6 U.S. CLIA-certified labs offering clinical ES. Approaches toward informed consent, data sharing, and results return vary widely among ES providers as do the overall potential merits and disadvantages of each, and more importantly, the balance between the two.
Keywords: Exome; Humans; Information Dissemination; Informed Consent; Morals; Organizational Policy; Practice Patterns, Physicians'; Sequence Analysis, DNA; United States

Recessive loss of function of the neuronal ubiquitin hydrolase UCHL1 leads to early-onset progressive neurodegeneration. - Bilguvar, Kaya; Tyagi, Navneet K; Ozkara, Cigdem; Tuysuz, Beyhan; Bakircioglu, Mehmet; Choi, Murim; Delil, Sakir; Çağlayan, Ahmet O; Baranoski, Jacob F; Erturk, Ozdem; Yalcinkaya, Cengiz; Karacorlu, Murat; et al. (Proc Natl Acad Sci U S A, 2013)
Ubiquitin C-terminal hydrolase-L1 (UCHL1), a neuron-specific de-ubiquitinating enzyme, is one of the most abundant proteins in the brain. We describe three siblings from a consanguineous union with a previously unreported early-onset progressive neurodegenerative syndrome featuring childhood onset blindness, cerebellar ataxia, nystagmus, dorsal column dysfuction, and spasticity with upper motor neuron dysfunction. Through homozygosity mapping of the affected individuals followed by whole-exome sequencing of the index case, we identified a previously undescribed homozygous missense mutation within the ubiquitin binding domain of UCHL1 (UCHL1(GLU7ALA)), shared by all affected subjects. As demonstrated by isothermal titration calorimetry, purified UCHL1(GLU7ALA), compared with WT, exhibited at least sevenfold reduced affinity for ubiquitin. In vitro, the mutation led to a near complete loss of UCHL1 hydrolase activity. The GLU7ALA variant is predicted to interfere with the substrate binding by restricting the proper positioning of the substrate for tunneling underneath the cross-over loop spanning the catalytic cleft of UCHL1. This interference with substrate binding, combined with near complete loss of hydrolase activity, resulted in a >100-fold reduction in the efficiency of UCHL1(GLU7ALA) relative to WT. These findings demonstrate a broad requirement of UCHL1 in the maintenance of the nervous system.
Keywords: Adult; Age of Onset; Amino Acid Sequence; Base Sequence; Child, Preschool; Exome; Female; Genes, Recessive; Homozygote; Humans; Hydrolysis; Male; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Nerve Degeneration; Neurons; Pedigree; Protein Binding; Sequence Analysis, DNA; Substrate Specificity; Syndrome; Thermodynamics; Ubiquitin; Ubiquitin Thiolesterase

Recessive mutations in DGKE cause atypical hemolytic-uremic syndrome. - Lemaire, Mathieu; Fremeaux-Bacchi, Veronique; Schaefer, Franz; Choi, Murim; Tang, Wai Ho; Le Quintrec, Moglie; Fakhouri, Fadi; Taque, Sophie; Nobili, François; Martinez, Frank; Ji, Weizhen; Overton, John D; et al. (Nat Genet, 2013)
Pathologic thrombosis is a major cause of mortality. Hemolytic-uremic syndrome (HUS) features episodes of small-vessel thrombosis resulting in microangiopathic hemolytic anemia, thrombocytopenia and renal failure. Atypical HUS (aHUS) can result from genetic or autoimmune factors that lead to pathologic complement cascade activation. Using exome sequencing, we identified recessive mutations in DGKE (encoding diacylglycerol kinase ɛ) that co-segregated with aHUS in nine unrelated kindreds, defining a distinctive Mendelian disease. Affected individuals present with aHUS before age 1 year, have persistent hypertension, hematuria and proteinuria (sometimes in the nephrotic range), and develop chronic kidney disease with age. DGKE is found in endothelium, platelets and podocytes. Arachidonic acid-containing diacylglycerols (DAG) activate protein kinase C (PKC), which promotes thrombosis, and DGKE normally inactivates DAG signaling. We infer that loss of DGKE function results in a prothrombotic state. These findings identify a new mechanism of pathologic thrombosis and kidney failure and have immediate implications for treating individuals with aHUS.
Keywords: Acute Kidney Injury; Atypical Hemolytic Uremic Syndrome; Child; Child, Preschool; Diacylglycerol Kinase; Exome; Female; Genes, Recessive; Hemolytic-Uremic Syndrome; Humans; Immunoenzyme Techniques; Infant; Male; Molecular Sequence Data; Mutation; Renal Insufficiency, Chronic; Thrombocytopenia; Thrombotic Microangiopathies

Recurrent gain-of-function mutation in PRKG1 causes thoracic aortic aneurysms and acute aortic dissections. - Guo, Dong-Chuan; Regalado, Ellen; Casteel, Darren E; Santos-Cortez, Regie L; Gong, Limin; Kim, Jeong Joo; Dyack, Sarah; Horne, S Gabrielle; Chang, Guijuan; Jondeau, Guillaume; Boileau, Catherine; Coselli, Joseph S; et al. (Am J Hum Genet, 2013)
Gene mutations that lead to decreased contraction of vascular smooth-muscle cells (SMCs) can cause inherited thoracic aortic aneurysms and dissections. Exome sequencing of distant relatives affected by thoracic aortic disease and subsequent Sanger sequencing of additional probands with familial thoracic aortic disease identified the same rare variant, PRKG1 c.530G>A (p.Arg177Gln), in four families. This mutation segregated with aortic disease in these families with a combined two-point LOD score of 7.88. The majority of affected individuals presented with acute aortic dissections (63%) at relatively young ages (mean 31 years, range 17-51 years). PRKG1 encodes type I cGMP-dependent protein kinase (PKG-1), which is activated upon binding of cGMP and controls SMC relaxation. Although the p.Arg177Gln alteration disrupts binding to the high-affinity cGMP binding site within the regulatory domain, the altered PKG-1 is constitutively active even in the absence of cGMP. The increased PKG-1 activity leads to decreased phosphorylation of the myosin regulatory light chain in fibroblasts and is predicted to cause decreased contraction of vascular SMCs. Thus, identification of a gain-of-function mutation in PRKG1 as a cause of thoracic aortic disease provides further evidence that proper SMC contractile function is critical for maintaining the integrity of the thoracic aorta throughout a lifetime.
Keywords: Acute Disease; Adolescent; Adult; Amino Acid Sequence; Aneurysm, Dissecting; Aorta, Thoracic; Aortic Aneurysm, Thoracic; Cyclic GMP; Cyclic GMP-Dependent Protein Kinase Type I; Exome; Female; Fibroblasts; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Molecular Sequence Data; Muscle Contraction; Muscle, Smooth, Vascular; Mutation; Myosin Light Chains; Pedigree

A recurrent PDGFRB mutation causes familial infantile myofibromatosis. - Cheung, Yee Him; Gayden, Tenzin; Campeau, Philippe M; LeDuc, Charles A; Russo, Donna; Nguyen, Van-Hung; Guo, Jiancheng; Qi, Ming; Guan, Yanfang; Albrecht, Steffen; Moroz, Brenda; Eldin, Karen W; et al. (Am J Hum Genet, 2013)
Infantile myofibromatosis (IM) is the most common benign fibrous tumor of soft tissues affecting young children. By using whole-exome sequencing, RNA sequencing, and targeted sequencing, we investigated germline and tumor DNA in individuals from four distinct families with the familial form of IM and in five simplex IM cases with no previous family history of this disease. We identified a germline mutation c.1681C>T (p.Arg561Cys) in platelet-derived growth factor receptor β (PDGFRB) in all 11 affected individuals with familial IM, although none of the five individuals with nonfamilial IM had mutations in this gene. We further identified a second heterozygous mutation in PDGFRB in two myofibromas from one of the affected familial cases, indicative of a potential second hit in this gene in the tumor. PDGFR-β promotes growth of mesenchymal cells, including blood vessels and smooth muscles, which are affected in IM. Our findings indicate p.Arg561Cys substitution in PDGFR-β as a cause of the dominant form of this disease. They provide a rationale for further investigations of this specific mutation and gene to assess the benefits of targeted therapies against PDGFR-β in aggressive life-threatening familial forms of the disease.
Keywords: Amino Acid Sequence; Female; Genes, Dominant; Genetic Association Studies; Germ-Line Mutation; Heterozygote; Humans; Male; Models, Molecular; Mutation, Missense; Myofibromatosis; Pedigree; Protein Structure, Tertiary; Receptor, Notch3; Receptor, Platelet-Derived Growth Factor beta; Receptors, Notch; Sequence Analysis, DNA

Replicative mechanisms for CNV formation are error prone. - Carvalho, Claudia M B; Pehlivan, Davut; Ramocki, Melissa B; Fang, Ping; Alleva, Benjamin; Franco, Luis M; Belmont, John W; Hastings, P J; Lupski, James R (Nat Genet, 2013)
We investigated 67 breakpoint junctions of gene copy number gains in 31 unrelated subjects. We observed a strikingly high frequency of small deletions and insertions (29%) apparently originating from polymerase slippage events, in addition to frameshifts and point mutations in homonucleotide runs (13%), at or flanking the breakpoint junctions of complex copy number variants. These single-nucleotide variants were generated concomitantly with the de novo complex genomic rearrangement (CGR) event. Our findings implicate low-fidelity, error-prone DNA polymerase activity in synthesis associated with DNA repair mechanisms as the cause of local increase in point mutation burden associated with human CGR.
Keywords: Base Sequence; DNA Breaks; DNA Copy Number Variations; DNA Repair; DNA Replication; Frameshift Mutation; Gene Rearrangement; Genetic Variation; Genotype; Humans; Sequence Analysis, DNA; Sequence Deletion

Reporting genomic sequencing results to ordering clinicians: incidental, but not exceptional. - Green, Robert C; Lupski, James R; Biesecker, Leslie G (JAMA, 2013)
Keywords: Disclosure; Genetic Predisposition to Disease; Genetic Testing; Humans; Incidental Findings; Mandatory Reporting; Mutation; Personal Autonomy; Risk; Sequence Analysis, DNA

Somatic and germline CACNA1D calcium channel mutations in aldosterone-producing adenomas and primary aldosteronism. - Scholl, Ute I; Goh, Gerald; Stölting, Gabriel; de Oliveira, Regina Campos; Choi, Murim; Overton, John D; Fonseca, Annabelle L; Korah, Reju; Starker, Lee F; Kunstman, John W; Prasad, Manju L; Hartung, Erum A; et al. (Nat Genet, 2013)
Adrenal aldosterone-producing adenomas (APAs) constitutively produce the salt-retaining hormone aldosterone and are a common cause of severe hypertension. Recurrent mutations in the potassium channel gene KCNJ5 that result in cell depolarization and Ca(2+) influx cause ∼40% of these tumors. We identified 5 somatic mutations (4 altering Gly403 and 1 altering Ile770) in CACNA1D, encoding a voltage-gated calcium channel, among 43 APAs without mutated KCNJ5. The altered residues lie in the S6 segments that line the channel pore. Both alterations result in channel activation at less depolarized potentials; Gly403 alterations also impair channel inactivation. These effects are inferred to cause increased Ca(2+) influx, which is a sufficient stimulus for aldosterone production and cell proliferation in adrenal glomerulosa. We also identified de novo germline mutations at identical positions in two children with a previously undescribed syndrome featuring primary aldosteronism and neuromuscular abnormalities. These findings implicate gain-of-function Ca(2+) channel mutations in APAs and primary aldosteronism.
Keywords: Adrenal Cortex Neoplasms; Adrenocortical Adenoma; Aldosterone; Amino Acid Sequence; Calcium Channels, L-Type; Cell Line; Child; Child, Preschool; Female; Germ-Line Mutation; Humans; Hyperaldosteronism; Male; Molecular Sequence Data; Mutation; Pedigree; Protein Conformation; Sequence Alignment

TM4SF20 ancestral deletion and susceptibility to a pediatric disorder of early language delay and cerebral white matter hyperintensities. - Wiszniewski, Wojciech; Hunter, Jill V; Hanchard, Neil A; Willer, Jason R; Shaw, Chad; Tian, Qi; Illner, Anna; Wang, Xueqing; Cheung, Sau W; Patel, Ankita; Campbell, Ian M; Gelowani, Violet; et al. (Am J Hum Genet, 2013)
White matter hyperintensities (WMHs) of the brain are important markers of aging and small-vessel disease. WMHs are rare in healthy children and, when observed, often occur with comorbid neuroinflammatory or vasculitic processes. Here, we describe a complex 4 kb deletion in 2q36.3 that segregates with early childhood communication disorders and WMH in 15 unrelated families predominantly from Southeast Asia. The premature brain aging phenotype with punctate and multifocal WMHs was observed in ~70% of young carrier parents who underwent brain MRI. The complex deletion removes the penultimate exon 3 of TM4SF20, a gene encoding a transmembrane protein of unknown function. Minigene analysis showed that the resultant net loss of an exon introduces a premature stop codon, which, in turn, leads to the generation of a stable protein that fails to target to the plasma membrane and accumulates in the cytoplasm. Finally, we report this deletion to be enriched in individuals of Vietnamese Kinh descent, with an allele frequency of about 1%, embedded in an ancestral haplotype. Our data point to a constellation of early language delay and WMH phenotypes, driven by a likely toxic mechanism of TM4SF20 truncation, and highlight the importance of understanding and managing population-specific low-frequency pathogenic alleles.
Keywords: Age of Onset; Aging, Premature; Asian Continental Ancestry Group; Base Sequence; Brain; Child; Child, Preschool; Chromosomes, Human, Pair 2; Exons; Female; Genetic Predisposition to Disease; Humans; Language Development Disorders; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Pedigree; Sequence Analysis, DNA; Sequence Deletion; Tetraspanins

Utilizing graph theory to select the largest set of unrelated individuals for genetic analysis. - Staples, Jeffrey; Nickerson, Deborah A; Below, Jennifer E (Genet Epidemiol, 2013)
Many statistical analyses of genetic data rely on the assumption of independence among samples. Consequently, relatedness is either modeled in the analysis or samples are removed to "clean" the data of any pairwise relatedness above a tolerated threshold. Current methods do not maximize the number of unrelated individuals retained for further analysis, and this is a needless loss of resources. We report a novel application of graph theory that identifies the maximum set of unrelated samples in any dataset given a user-defined threshold of relatedness as well as all networks of related samples. We have implemented this method into an open source program called Pedigree Reconstruction and Identification of a Maximum Unrelated Set, PRIMUS. We show that PRIMUS outperforms the three existing methods, allowing researchers to retain up to 50% more unrelated samples. A unique strength of PRIMUS is its ability to weight the maximum clique selection using additional criteria (e.g. affected status and data missingness). PRIMUS is a permanent solution to identifying the maximum number of unrelated samples for a genetic analysis.
Keywords: Algorithms; Genome-Wide Association Study; HapMap Project; Humans; Models, Theoretical

Whole-exome sequencing identified a patient with TMCO1 defect syndrome and expands the phenotic spectrum. - Caglayan, A O; Per, H; Akgumus, G; Gumus, H; Baranoski, J; Canpolat, M; Calik, M; Yikilmaz, A; Bilguvar, K; Kumandas, S; Gunel, M (Clin Genet, 2013)
Keywords: Abnormalities, Multiple; Base Sequence; Child; Consanguinity; Exome; Humans; Male; Membrane Proteins; Pedigree; Phenotype; Sequence Analysis, DNA; Syndrome

Whole-exome sequencing reveals somatic mutations in HRAS and KRAS, which cause nevus sebaceus. - Levinsohn, Jonathan L; Tian, Li C; Boyden, Lynn M; McNiff, Jennifer M; Narayan, Deepak; Loring, Erin S; Yun, Duri; Sugarman, Jeffrey L; Overton, John D; Mane, Shrikant M; Lifton, Richard P; Paller, Amy S; et al. (J Invest Dermatol, 2013)
Keywords: Adolescent; Adult; Amino Acid Sequence; Biopsy; Child; Child, Preschool; Cohort Studies; Epidermis; Exome; Humans; Infant; Middle Aged; Molecular Sequence Data; Mutation; Nevus, Sebaceous of Jadassohn; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); ras Proteins; Sequence Analysis, DNA; Young Adult

Whole-genome analysis reveals that mutations in inositol polyphosphate phosphatase-like 1 cause opsismodysplasia. - Below, Jennifer E; Earl, Dawn L; Shively, Kathryn M; McMillin, Margaret J; Smith, Joshua D; Turner, Emily H; Stephan, Mark J; Al-Gazali, Lihadh I; Hertecant, Jozef L; Chitayat, David; Unger, Sheila; Cohn, Daniel H; et al. (Am J Hum Genet, 2013)
Opsismodysplasia is a rare, autosomal-recessive skeletal dysplasia characterized by short stature, characteristic facial features, and in some cases severe renal phosphate wasting. We used linkage analysis and whole-genome sequencing of a consanguineous trio to discover that mutations in inositol polyphosphate phosphatase-like 1 (INPPL1) cause opsismodysplasia with or without renal phosphate wasting. Evaluation of 12 families with opsismodysplasia revealed that INPPL1 mutations explain ~60% of cases overall, including both of the families in our cohort with more than one affected child and 50% of the simplex cases.
Keywords: Child; Child, Preschool; Female; Genome, Human; Humans; Infant; Infant, Newborn; Male; Mutation; Osteochondrodysplasias; Phosphatidylinositol-3,4,5-Trisphosphate 5-Phosphatases; Phosphoric Monoester Hydrolases

The Centers for Mendelian Genomics: a new large-scale initiative to identify the genes underlying rare Mendelian conditions. - Bamshad, Michael J; Shendure, Jay A; Valle, David; Hamosh, Ada; Lupski, James R; Gibbs, Richard A; Boerwinkle, Eric; Lifton, Richard P; Gerstein, Mark; Günel, Murat; Mane, Shrikant; Nickerson, Deborah A (Am J Med Genet A, 2012)
Next generation exome sequencing (ES) and whole genome sequencing (WGS) are new powerful tools for discovering the gene(s) that underlie Mendelian disorders. To accelerate these discoveries, the National Institutes of Health has established three Centers for Mendelian Genomics (CMGs): the Center for Mendelian Genomics at the University of Washington; the Center for Mendelian Genomics at Yale University; and the Baylor-Johns Hopkins Center for Mendelian Genomics at Baylor College of Medicine and Johns Hopkins University. The CMGs will provide ES/WGS and extensive analysis expertise at no cost to collaborating investigators where the causal gene(s) for a Mendelian phenotype has yet to be uncovered. Over the next few years and in collaboration with the global human genetics community, the CMGs hope to facilitate the identification of the genes underlying a very large fraction of all Mendelian disorders; see http://mendelian.org.
Keywords: Academies and Institutes; Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Genome-Wide Association Study; Genomics; High-Throughput Nucleotide Sequencing; Humans

Digenic inheritance of an SMCHD1 mutation and an FSHD-permissive D4Z4 allele causes facioscapulohumeral muscular dystrophy type 2. - Lemmers, Richard J L F; Tawil, Rabi; Petek, Lisa M; Balog, Judit; Block, Gregory J; Santen, Gijs W E; Amell, Amanda M; van der Vliet, Patrick J; Almomani, Rowida; Straasheijm, Kirsten R; Krom, Yvonne D; Klooster, Rinse; et al. (Nat Genet, 2012)
Facioscapulohumeral dystrophy (FSHD) is characterized by chromatin relaxation of the D4Z4 macrosatellite array on chromosome 4 and expression of the D4Z4-encoded DUX4 gene in skeletal muscle. The more common form, autosomal dominant FSHD1, is caused by contraction of the D4Z4 array, whereas the genetic determinants and inheritance of D4Z4 array contraction-independent FSHD2 are unclear. Here, we show that mutations in SMCHD1 (encoding structural maintenance of chromosomes flexible hinge domain containing 1) on chromosome 18 reduce SMCHD1 protein levels and segregate with genome-wide D4Z4 CpG hypomethylation in human kindreds. FSHD2 occurs in individuals who inherited both the SMCHD1 mutation and a normal-sized D4Z4 array on a chromosome 4 haplotype permissive for DUX4 expression. Reducing SMCHD1 levels in skeletal muscle results in D4Z4 contraction-independent DUX4 expression. Our study identifies SMCHD1 as an epigenetic modifier of the D4Z4 metastable epiallele and as a causal genetic determinant of FSHD2 and possibly other human diseases subject to epigenetic regulation.
Keywords: Adult; Aged; Chromosomal Proteins, Non-Histone; Chromosomes, Human, Pair 18; CpG Islands; DNA Methylation; Epigenesis, Genetic; Female; Haplotypes; Heredity; Homeodomain Proteins; Humans; Male; Middle Aged; Muscular Dystrophy, Facioscapulohumeral; Mutation

Facioscapulohumeral muscular dystrophy: consequences of chromatin relaxation. - van der Maarel, Silvère M; Miller, Daniel G; Tawil, Rabi; Filippova, Galina N; Tapscott, Stephen J (Curr Opin Neurol, 2012)
PURPOSE OF REVIEW: In recent years, we have seen remarkable progress in our understanding of the disease mechanism underlying facioscapulohumeral muscular dystrophy (FSHD). The purpose of this review is to provide a comprehensive overview of our current understanding of the disease mechanism and to discuss the observations supporting the possibility of a developmental defect in this disorder. RECENT FINDINGS: In the majority of cases, FSHD is caused by contraction of the D4Z4 repeat array (FSHD1). This results in local chromatin relaxation and stable expression of the DUX4 retrogene in skeletal muscle, but only when a polymorphic DUX4 polyadenylation signal is present. In some cases (FSHD2), D4Z4 chromatin relaxation and stable DUX4 expression occur in the absence of D4Z4 array contraction. DUX4 is a germline transcription factor and its expression in skeletal muscle leads to activation of early stem cell and germline programs and transcriptional activation of retroelements. SUMMARY: Recent studies have provided a plausible disease mechanism for FSHD in which FSHD results from inappropriate expression of the germline transcription factor DUX4. The genes regulated by DUX4 suggest several mechanisms of muscle damage, and provide potential biomarkers and therapeutic targets that should be investigated in future studies.
Keywords: Animals; Chromatin; Homeodomain Proteins; Humans; Muscle, Skeletal; Muscular Dystrophy, Facioscapulohumeral; Transcription, Genetic

A fast and noise-resilient approach to detect rare-variant associations with deep sequencing data for complex disorders. - Cheung, Yee Him; Wang, Gao; Leal, Suzanne M; Wang, Shuang (Genet Epidemiol, 2012)
Next generation sequencing technology has enabled the paradigm shift in genetic association studies from the common disease/common variant to common disease/rare-variant hypothesis. Analyzing individual rare variants is known to be underpowered; therefore association methods have been developed that aggregate variants across a genetic region, which for exome sequencing is usually a gene. The foreseeable widespread use of whole genome sequencing poses new challenges in statistical analysis. It calls for new rare-variant association methods that are statistically powerful, robust against high levels of noise due to inclusion of noncausal variants, and yet computationally efficient. We propose a simple and powerful statistic that combines the disease-associated P-values of individual variants using a weight that is the inverse of the expected standard deviation of the allele frequencies under the null. This approach, dubbed as Sigma-P method, is extremely robust to the inclusion of a high proportion of noncausal variants and is also powerful when both detrimental and protective variants are present within a genetic region. The performance of the Sigma-P method was tested using simulated data based on realistic population demographic and disease models and its power was compared to several previously published methods. The results demonstrate that this method generally outperforms other rare-variant association methods over a wide range of models. Additionally, sequence data on the ANGPTL family of genes from the Dallas Heart Study were tested for associations with nine metabolic traits and both known and novel putative associations were uncovered using the Sigma-P method.
Keywords: Angiopoietin-like 4 Protein; Angiopoietin-like Proteins; Angiopoietins; Case-Control Studies; Data Interpretation, Statistical; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; High-Throughput Nucleotide Sequencing; Humans; Metabolism; Sequence Analysis, DNA; Texas; Triglycerides

Haploinsufficiency of SF3B4, a component of the pre-mRNA spliceosomal complex, causes Nager syndrome. - Bernier, Francois P; Caluseriu, Oana; Ng, Sarah; Schwartzentruber, Jeremy; Buckingham, Kati J; Innes, A Micheil; Jabs, Ethylin Wang; Innis, Jeffrey W; Schuette, Jane L; Gorski, Jerome L; Byers, Peter H; Andelfinger, Gregor; et al. (Am J Hum Genet, 2012)
Nager syndrome, first described more than 60 years ago, is the archetype of a class of disorders called the acrofacial dysostoses, which are characterized by craniofacial and limb malformations. Despite intensive efforts, no gene for Nager syndrome has yet been identified. In an international collaboration, FORGE Canada and the National Institutes of Health Centers for Mendelian Genomics used exome sequencing as a discovery tool and found that mutations in SF3B4, a component of the U2 pre-mRNA spliceosomal complex, cause Nager syndrome. After Sanger sequencing of SF3B4 in a validation cohort, 20 of 35 (57%) families affected by Nager syndrome had 1 of 18 different mutations, nearly all of which were frameshifts. These results suggest that most cases of Nager syndrome are caused by haploinsufficiency of SF3B4. Our findings add Nager syndrome to a growing list of disorders caused by mutations in genes that encode major components of the spliceosome and also highlight the synergistic potential of international collaboration when exome sequencing is applied in the search for genes responsible for rare Mendelian phenotypes.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Exome; Female; Haploinsufficiency; Humans; Limb Deformities, Congenital; Male; Mandibulofacial Dysostosis; Mutation; Reproducibility of Results; RNA Precursors; RNA Splicing Factors; RNA-Binding Proteins; Spliceosomes; Young Adult

Human genome sequencing in health and disease. - Gonzaga-Jauregui, Claudia; Lupski, James R; Gibbs, Richard A (Annu Rev Med, 2012)
Following the "finished," euchromatic, haploid human reference genome sequence, the rapid development of novel, faster, and cheaper sequencing technologies is making possible the era of personalized human genomics. Personal diploid human genome sequences have been generated, and each has contributed to our better understanding of variation in the human genome. We have consequently begun to appreciate the vastness of individual genetic variation from single nucleotide to structural variants. Translation of genome-scale variation into medically useful information is, however, in its infancy. This review summarizes the initial steps undertaken in clinical implementation of personal genome information, and describes the application of whole-genome and exome sequencing to identify the cause of genetic diseases and to suggest adjuvant therapies. Better analysis tools and a deeper understanding of the biology of our genome are necessary in order to decipher, interpret, and optimize clinical utility of what the variation in the human genome can teach us. Personal genome sequencing may eventually become an instrument of common medical practice, providing information that assists in the formulation of a differential diagnosis. We outline herein some of the remaining challenges.
Keywords: Genetic Diseases, Inborn; Genetic Privacy; Genome, Human; HapMap Project; Human Genome Project; Humans

Loss-of-function mutations in TGFB2 cause a syndromic presentation of thoracic aortic aneurysm. - Lindsay, Mark E; Schepers, Dorien; Bolar, Nikhita Ajit; Doyle, Jefferson J; Gallo, Elena; Fert-Bober, Justyna; Kempers, Marlies J E; Fishman, Elliot K; Chen, Yichun; Myers, Loretha; Bjeda, Djahita; Oswald, Gretchen; et al. (Nat Genet, 2012)
Loeys-Dietz syndrome (LDS) associates with a tissue signature for high transforming growth factor (TGF)-β signaling but is often caused by heterozygous mutations in genes encoding positive effectors of TGF-β signaling, including either subunit of the TGF-β receptor or SMAD3, thereby engendering controversy regarding the mechanism of disease. Here, we report heterozygous mutations or deletions in the gene encoding the TGF-β2 ligand for a phenotype within the LDS spectrum and show upregulation of TGF-β signaling in aortic tissue from affected individuals. Furthermore, haploinsufficient Tgfb2(+/-) mice have aortic root aneurysm and biochemical evidence of increased canonical and noncanonical TGF-β signaling. Mice that harbor both a mutant Marfan syndrome (MFS) allele (Fbn1(C1039G/+)) and Tgfb2 haploinsufficiency show increased TGF-β signaling and phenotypic worsening in association with normalization of TGF-β2 expression and high expression of TGF-β1. Taken together, these data support the hypothesis that compensatory autocrine and/or paracrine events contribute to the pathogenesis of TGF-β-mediated vasculopathies.
Keywords: Animals; Aortic Aneurysm, Thoracic; Disease Models, Animal; Female; Fibrillin-1; Fibrillins; Haploinsufficiency; Humans; Loeys-Dietz Syndrome; Male; Marfan Syndrome; Mice; Mice, Knockout; Mice, Mutant Strains; Microfilament Proteins; Mutation; Pedigree; Phenotype; Signal Transduction; Syndrome; Transforming Growth Factor beta2

Mutations in the TGF-β repressor SKI cause Shprintzen-Goldberg syndrome with aortic aneurysm. - Doyle, Alexander J; Doyle, Jefferson J; Bessling, Seneca L; Maragh, Samantha; Lindsay, Mark E; Schepers, Dorien; Gillis, Elisabeth; Mortier, Geert; Homfray, Tessa; Sauls, Kimberly; Norris, Russell A; Huso, Nicholas D; et al. (Nat Genet, 2012)
Elevated transforming growth factor (TGF)-β signaling has been implicated in the pathogenesis of syndromic presentations of aortic aneurysm, including Marfan syndrome (MFS) and Loeys-Dietz syndrome (LDS). However, the location and character of many of the causal mutations in LDS intuitively imply diminished TGF-β signaling. Taken together, these data have engendered controversy regarding the specific role of TGF-β in disease pathogenesis. Shprintzen-Goldberg syndrome (SGS) has considerable phenotypic overlap with MFS and LDS, including aortic aneurysm. We identified causative variation in ten individuals with SGS in the proto-oncogene SKI, a known repressor of TGF-β activity. Cultured dermal fibroblasts from affected individuals showed enhanced activation of TGF-β signaling cascades and higher expression of TGF-β-responsive genes relative to control cells. Morpholino-induced silencing of SKI paralogs in zebrafish recapitulated abnormalities seen in humans with SGS. These data support the conclusions that increased TGF-β signaling is the mechanism underlying SGS and that high signaling contributes to multiple syndromic presentations of aortic aneurysm.
Keywords: Animals; Aortic Aneurysm; Arachnodactyly; Cells, Cultured; Craniosynostoses; DNA-Binding Proteins; Fibroblasts; Humans; Loeys-Dietz Syndrome; Marfan Syndrome; Mice; Mutation; Phenotype; Phosphorylation; Proto-Oncogene Proteins; Signal Transduction; Transforming Growth Factor beta; Zebrafish

Next generation analytic tools for large scale genetic epidemiology studies of complex diseases. - Mechanic, Leah E; Chen, Huann-Sheng; Amos, Christopher I; Chatterjee, Nilanjan; Cox, Nancy J; Divi, Rao L; Fan, Ruzong; Harris, Emily L; Jacobs, Kevin; Kraft, Peter; Leal, Suzanne M; McAllister, Kimberly; et al. (Genet Epidemiol, 2012)
Over the past several years, genome-wide association studies (GWAS) have succeeded in identifying hundreds of genetic markers associated with common diseases. However, most of these markers confer relatively small increments of risk and explain only a small proportion of familial clustering. To identify obstacles to future progress in genetic epidemiology research and provide recommendations to NIH for overcoming these barriers, the National Cancer Institute sponsored a workshop entitled "Next Generation Analytic Tools for Large-Scale Genetic Epidemiology Studies of Complex Diseases" on September 15-16, 2010. The goal of the workshop was to facilitate discussions on (1) statistical strategies and methods to efficiently identify genetic and environmental factors contributing to the risk of complex disease; and (2) how to develop, apply, and evaluate these strategies for the design, analysis, and interpretation of large-scale complex disease association studies in order to guide NIH in setting the future agenda in this area of research. The workshop was organized as a series of short presentations covering scientific (gene-gene and gene-environment interaction, complex phenotypes, and rare variants and next generation sequencing) and methodological (simulation modeling and computational resources and data management) topic areas. Specific needs to advance the field were identified during each session and are summarized.
Keywords: Data Mining; Gene-Environment Interaction; Genetic Variation; Genome-Wide Association Study; Humans; Molecular Epidemiology; National Institutes of Health (U.S.); Neoplasms; Phenotype; United States

Phenotype diversity in type 1 Gaucher disease: discovering the genetic basis of Gaucher disease/hematologic malignancy phenotype by individual genome analysis. - Lo, Sarah M; Choi, Murim; Liu, Jun; Jain, Dhanpat; Boot, Rolf G; Kallemeijn, Wouter W; Aerts, Johannes M F G; Pashankar, Farzana; Kupfer, Gary M; Mane, Shrikant; Lifton, Richard P; Mistry, Pramod K (Blood, 2012)
Gaucher disease (GD), an inherited macrophage glycosphingolipidosis, manifests with an extraordinary variety of phenotypes that show imperfect correlation with mutations in the GBA gene. In addition to the classic manifestations, patients suffer from increased susceptibility to hematologic and nonhematologic malignancies. The mechanism(s) underlying malignancy in GD is not known, but is postulated to be secondary to macrophage dysfunction and immune dysregulation arising from lysosomal accumulation of glucocerebroside. However, there is weak correlation between GD/cancer phenotype and the systemic burden of glucocerebroside-laden macrophages. Therefore, we hypothesized that genetic modifier(s) may underlie the GD/cancer phenotype. In the present study, the genetic basis of GD/T-cell acute lymphoblastic lymphoma in 2 affected siblings was deciphered through genomic analysis. GBA gene sequencing revealed homozygosity for a novel mutation, D137N. Whole-exome capture and massively parallel sequencing combined with homozygosity mapping identified a homozygous novel mutation in the MSH6 gene that leads to constitutional mismatch repair deficiency syndrome and increased cancer risk. Enzyme studies demonstrated that the D137N mutation in GBA is a pathogenic mutation, and immunohistochemistry confirmed the absence of the MSH6 protein. Therefore, precise phenotype annotation followed by individual genome analysis has the potential to identify genetic modifiers of GD, facilitate personalized management, and provide novel insights into disease pathophysiology.
Keywords: Adult; beta-Glucosidase; Child; Child, Preschool; Female; Gaucher Disease; Genome, Human; Hematologic Neoplasms; Humans; Individuality; Male; Pedigree; Phenotype; Sequence Analysis, DNA; Siblings

SEQCHIP: a powerful method to integrate sequence and genotype data for the detection of rare variant associations. - Liu, Dajiang J; Leal, Suzanne M (Bioinformatics, 2012)
MOTIVATION: Next-generation sequencing greatly increases the capacity to detect rare-variant complex-trait associations. However, it is still expensive to sequence a large number of samples and therefore often small datasets are used. Given cost constraints, a potentially more powerful two-step strategy is to sequence a subset of the sample to discover variants, and genotype the identified variants in the remaining sample. If only cases are sequenced, directly combining sequence and genotype data will lead to inflated type-I errors in rare-variant association analysis. Although several methods have been developed to correct for the bias, they are either underpowered or theoretically invalid. We proposed a new method SEQCHIP to integrate genotype and sequence data, which can be used with most existing rare-variant tests. RESULTS: It is demonstrated using both simulated and real datasets that the SEQCHIP method has controlled type-I errors, and is substantially more powerful than all other currently available methods. AVAILABILITY: SEQCHIP is implemented in an R-Package and is available at http://linkage.rockefeller.edu/suzanne/seqchip/Seqchip.html.
Keywords: Adenoma; Case-Control Studies; Colorectal Neoplasms; Genetic Association Studies; Genetic Variation; Genotype; Humans; Phenotype; Sequence Analysis, DNA; Software

SimRare: a program to generate and analyze sequence-based data for association studies of quantitative and qualitative traits. - Li, Biao; Wang, Gao; Leal, Suzanne M (Bioinformatics, 2012)
MOTIVATION: Currently, there is great interest in detecting complex trait rare variant associations using next-generation sequence data. On a monthly basis, new rare variant association methods are published. It is difficult to evaluate these methods because there is no standard to generate data and often comparisons are biased. In order to fairly compare rare variant association methods, it is necessary to generate data using realistic population demographic and phenotypic models. RESULT: SimRare is an interactive program that integrates generation of rare variant genotype/phenotype data and evaluation of association methods using a unified platform. Variant data are generated for gene regions using forward-time simulation that incorporates realistic population demographic and evolutionary scenarios. Phenotype data can be obtained for both case-control and quantitative traits. SimRare has a user-friendly interface that allows for easy entry of genetic and phenotypic parameters. Novel rare variant association methods implemented in R can also be imported into SimRare, to evaluate their performance and compare results, e.g. power and Type I error, with other currently available methods both numerically and graphically.
Keywords: Genetic Association Studies; Genetic Variation; Humans; Phenotype; Quantitative Trait, Heritable; Software

A unified method for detecting secondary trait associations with rare variants: application to sequence data. - Liu, Dajiang J; Leal, Suzanne M (PLoS Genet, 2012)
Next-generation sequencing has made possible the detection of rare variant (RV) associations with quantitative traits (QT). Due to high sequencing cost, many studies can only sequence a modest number of selected samples with extreme QT. Therefore association testing in individual studies can be underpowered. Besides the primary trait, many clinically important secondary traits are often measured. It is highly beneficial if multiple studies can be jointly analyzed for detecting associations with commonly measured traits. However, analyzing secondary traits in selected samples can be biased if sample ascertainment is not properly modeled. Some methods exist for analyzing secondary traits in selected samples, where some burden tests can be implemented. However p-values can only be evaluated analytically via asymptotic approximations, which may not be accurate. Additionally, potentially more powerful sequence kernel association tests, variable selection-based methods, and burden tests that require permutations cannot be incorporated. To overcome these limitations, we developed a unified method for analyzing secondary trait associations with RVs (STAR) in selected samples, incorporating all RV tests. Statistical significance can be evaluated either through permutations or analytically. STAR makes it possible to apply more powerful RV tests to analyze secondary trait associations. It also enables jointly analyzing multiple cohorts ascertained under different study designs, which greatly boosts power. The performance of STAR and commonly used RV association tests were comprehensively evaluated using simulation studies. STAR was also implemented to analyze a dataset from the SardiNIA project where samples with extreme low-density lipoprotein levels were sequenced. A significant association between LDLR and systolic blood pressure was identified, which is supported by pharmacogenetic studies. In summary, for sequencing studies, STAR is an important tool for detecting secondary-trait RV associations.
Keywords: Blood Pressure; Computer Simulation; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Italy; Lipoproteins, LDL; Models, Genetic; Phenotype; Quantitative Trait Loci; Software

Clan genomics and the complex architecture of human disease. - Lupski, James R; Belmont, John W; Boerwinkle, Eric; Gibbs, Richard A (Cell, 2011)
Human diseases are caused by alleles that encompass the full range of variant types, from single-nucleotide changes to copy-number variants, and these variations span a broad frequency spectrum, from the very rare to the common. The picture emerging from analysis of whole-genome sequences, the 1000 Genomes Project pilot studies, and targeted genomic sequencing derived from very large sample sizes reveals an abundance of rare and private variants. One implication of this realization is that recent mutation may have a greater influence on disease susceptibility or protection than is conferred by variations that arose in distant ancestors.
Keywords: Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome, Human; Genomics; Humans; Pedigree; Pilot Projects; Precision Medicine

GENOME-WIDE ASSOCIATION MAPPING AND RARE ALLELES: FROM POPULATION GENOMICS TO PERSONALIZED MEDICINE - Session Introduction. - DE LA Vega, Francisco M; Bustamante, Carlos D; Leal, Suzanne M (Pac Symp Biocomput, 2011)
Genome-wide associations studies (GWAS) have been very successful in identifying common genetic variation associated to numerous complex diseases [1]. However, most of the identified common genetic variants appear to confer modest risk and few causal alleles have been identified [2]. Furthermore, these associations account for a small portion of the total heritability of inherited disease variation [1]. This has led to the reexamination of the contribution of environment, gene-gene and gene-environment interactions, and rare genetic variants in complex diseases [1, 3, 4]. There is strong evidence that rare variants play an important role in complex disease etiology and may have larger genetic effects than common variants [2]. Currently, much of what we know regarding the contribution of rare genetic variants to disease risk is based on a limited number of phenotypes and candidate genes. However, rapid advancement of second generation sequencing technologies will invariably lead to widespread association studies comparing whole exome and eventually whole genome sequencing of cases and controls. A tremendous challenge for enabling these "next generation" medical genomic studies is developing statistical approaches for correlating rare genetic variants with disease outcome. The analysis of rare variants is challenging since methods used for common variants are woefully underpowered. Therefore, methods that can deal with genetic heterogeneity at the trait-associated locus have been developed to analyze rare variants. These methods instead analyzing individual variants analyze variants within a region/gene as a group and usually rely on collapsing. They can be applied to both in cases vs. controls and quantitative trait studies are needed. The paper of Bansal et al. in this volume describes the application of a number of statistical methods for testing associations between rare variants in two genes to obesity. The authors considered the relative merits of the different methods as well as important implementation details, such as the leveraging of genomic annotations and determining p-values. Knowledge of haplotypes can increase the power of GWAS studies and also highlight associations that are impossible to detect without haplotype phase (e.g. loss of heterozygosity). Even more complicated phase-dependent interactions of variants in linkage equilibrium have also been suggested as possible causes of missing heritability. In their work, Hallsorsson et al. formulate algorithmic strategies for haplotype phasing by multi-assembly of shared haplotypes from next-generation sequencing data. These methods would allow testing haplotypes harboring rare variants for association and potentially increase their explanatory power. Since single SNP tests are often underpowered in rare variant association analysis, Zeggini and Asimit propose a locus-based method that has high power in the presence of rare variants and that incorporate base quality scores available for sequencing data. Their results suggest that this multi-marker approach may be best suited for smaller regions, or after some filtering to reduce the number of SNPs that are jointly tested to reduce loss of power due to multiple-testing adjustments. Finally, the paper of Zhou et al., presents a penalized regression framework for association testing on sequence data, in the presence of both common and rare variants. This method also introduces the use of weights to incorporate available biological information on the variants. Although these tactics improve both false positive and false negative rates, they represent an incremental development and there is still significant room for improvement. With the development of sequencing technologies and methods to detect complex trait rare variant associations many new and exciting discovery are imminent. The analysis of rare variants is still in its infancy and the next few years promises to produce many new methods to meet the special demands of analyzing this type of data. Note from Publisher: This article contains the abstract and references.